Impact of early Coronavirus Disease 2019 pandemic on pediatric cardiac surgery in China - Shi, G.; Huang, J.; Pi, M.; Chen, X.; Li, X.; Ding, Y.; Zhang, H.; Xiao, D.; Huang, G.; Ming, T.; Huang, P.; Liu, C.; et al. (Journal of Thoracic and Cardiovascular Surgery, 2021)
Objective: This study aimed to provide an insight into the impact of the early outbreak of the novel Coronavirus Disease 2019 on the care management for patients with congenital heart disease. Methods: This study respectively enrolled a cohort of surgical patients who underwent surgery in 2018 (group I), 2019 (group II), and 2020 (group III) and a cohort of follow-up patients who had follow-up in 2017 (group A), 2018 (group B), and 2019 (group C) in 13 children hospitals. Results: During the Coronavirus Disease 2019 era, there was a significant decrease in total surgical volume and a change in case mix in terms of an increase in the proportion of emergency operations. Decrease in migration scale index was correlated to the decrease in both surgical volume (r = 0.64, P = .02) and outpatient visit volume (r = 0.61, P = .03). There was a significantly higher proportion of patients who had follow-up through the internet or phone in group C (26.4% vs 9.6% in group B and 8.9% in group A; P < .0001). There was no statistical difference in death or rehospitalization among the 3 follow-up groups (P =. 49). There was higher parents' anxiety score (P < .0001) and more use of telemedicine (P = .004) in group C compared with groups A and B. Conclusions: The Coronavirus Disease 2019 pandemic has resulted in a considerable decrease in total surgical volume and a change of case mix, which seems to be related to the strict traffic ban. Follow-up through the online medical service appears to be an effective alternative to the conventional method.
Keywords: information processing device; anxiety; aortic arch interruption; aortic coarctation; article; atrioventricular septal defect; case mix; child; childhood mortality; China; clinical article; clinical outcome; cohort analysis; congenital heart disease; controlled study; coronavirus disease 2019; COVID-19 nucleic acid testing; COVID-19 serological testing; data analysis software; elective surgery; Fallot tetralogy; female; follow up; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; heart surgery; heart ventricle septum defect; hospital readmission; human; infant; internet access; lung vein drainage anomaly; male; migration; observational study; pandemic; parent; patent atrial duct; pediatric surgery; priority journal; pulmonary valve atresia; pulmonary vein malformation; scoring system; surgical patient; surgical volume; telemedicine

Contrast-induced encephalopathy in an infant - Gonzalez-Pardo, O.; Ordoñez, A.; Roa, C. (Radiology Case Reports, 2021)
Contrast-induced encephalopathy (CIE) is a well-known but rare complication following contrast media administration. Its nonspecific clinical manifestations hinder diagnosis, particularly in the pediatric population. The majority of cases are reversible, with clinical improvement and resolution of signs noted on diagnostic imaging. Here, we report the case of a 2-month-old patient with a history of complex cardiovascular disease who presented with a single episode of seizure after undergoing cardiac catheterization with nonionic iodinated contrast media. CIE is diagnosed based on the signs and symptoms exhibited by the patient and the findings on plain head computed tomography (CT) scan. Subsequently, the absence of neurological symptoms and disappearance of the imaging alterations on a control CT are documented.
Keywords: furosemide; iopromide; spironolactone; article; body weight; brain disease; cardiopulmonary insufficiency; case report; cava vein; clinical article; clonic seizure; computer assisted tomography; congenital heart disease; contrast induced encephalopathy; cyanosis; differential diagnosis; drug induced disease; female; frontal lobe; good general condition; great vessels transposition; heart atrium septum defect; heart catheterization; heart massage; heart right ventricle double outlet; heart single ventricle; hemodynamics; human; infant; lung artery banding; occipital lobe; parietal lobe; pediatric cardiology; physical examination; priority journal; sucking; surgical technique; symptom

Defining a new normal: A qualitative exploration of the parent experience during the single ventricle congenital heart disease interstage period - Elliott, M.; Erickson, L.; Russell, C.L.; Chrisman, M.; Gross Toalson, J.; Emerson, A. (Journal of advanced nursing, 2021)
AIM: To explore parents' experience of transition in the period between the palliative cardiac surgeries (i.e., the interstage period) of an infant with single ventricle congenital heart disease. DESIGN: We conducted an exploratory naturalistic inquiry using a qualitative descriptive approach. METHODS: A purposive sample of 11 parents of children with single ventricle disease was selected among families that participated in an interstage-period parental home monitoring program during the past 2 years. Interviews and field observations were conducted September-October 2019, and data were analyzed for themes. Analysis of data was inductive, although study questions and the interpretation of results were informed by Meleis' transition theory. RESULTS: Parents described the experience of transition in interstage as a striving for normality, a theme that was clustered in subthemes of home, self, and infant. CONCLUSION: Parents' experiences of striving for normality indicated a need for more targeted efforts to address parents' psychosocial needs during the highly stressful interstage transition. IMPACT: This research underscored the complexity of parents' psychosocial support needs on returning home after their child's first palliative surgery. The findings also suggest need for examination of the transition following the second palliative heart surgery, when the home monitoring program is withdrawn. Understanding parent needs will help guide healthcare teams in developing ways to support parents as they adjust to home, self, and child.
Keywords: article; child; exploratory research; heart single ventricle; heart surgery; home monitoring; human; human tissue; infant; interview; naturalistic inquiry; nursing; palliative therapy; physiological stress; psychosocial care; purposive sample; surgery; theoretical study

Assessment and Treatment of a Young Adult with Congenital Heart Disease and ADHD - Hammerness, P.G.; Cassidy, A.R.; Potts, H.; Richardson, A.; Fogler, J.; Daly, K.P.; Augustyn, M. (Journal of developmental and behavioral pediatrics : JDBP, 2021)
CASE: Phillip is a young man born with hypoplastic left heart syndrome referred to your practice for a range of mental health concerns. He underwent palliation to an extracardiac Fontan in infancy and experienced multiple complications over the next decade including valvular regurgitation and arrhythmias necessitating a pacemaker. Phillip continued to have systolic heart failure with New York Heart Association class II symptoms, managed with 4 medications and anticoagulation.Despite this complex history, Phillip had intact cognitive abilities, achieved typical milestones, and performed well academically in secondary school. His first year of college proved to be more challenging, and Phillip presented to the outpatient psychiatry service with an acute depressive episode. His family history included depression, without known attention-deficit/hyperactivity disorder (ADHD). Treatment, including a selective serotonin reuptake inhibitor, cognitive behavioral therapy, and family support, led to near resolution of his symptoms of depression.In subsequent appointments, Phillip described a long history of inattention and disorganization with onset in childhood. This contributed to the decision to leave college, despite remission of symptoms of depression. Phillip was unable to study for any extended period without "perfect conditions," described as the absence of potential distractions except for background music. Despite attempts to maintain "perfect conditions," Phillip was often off task and "hyperfocusing" on irrelevant topics. Phillip struggled with planning and time management and would misplace items daily. Moreover, although the importance of self-care was well understood, Phillip often forgot to take his cardiac medication or to exercise, and he admitted to inconsistent sleep habits because of losing track of time.Based on a comprehensive psychiatric evaluation including retrospective report from a parent, Phillip was diagnosed with ADHD, coexisting with major depressive disorder, in remission. Significant ADHD symptoms were documented by interview, self-report, and administration of an abbreviated neuropsychological battery.Considering concerns regarding use of stimulants in a patient with congenital heart disease, including death, stroke, and myocardial infarction,1,2 how would you assess the risks-benefits of use of stimulants with Phillip? REFERENCES: 1. Wilens TE, Prince JB, Spencer TJ, et al. Stimulants and sudden death: what is a physician to do? Pediatrics. 2006;118:1215-1219.2. Zito JM, Burcu M. Stimulants and pediatric cardiovascular risk. J Child Adolesc Psychopharmacol. 2017;27:538-545.
Keywords: adult; anticoagulation; article; attention deficit disorder; cardiac rhythm management device; cerebrovascular accident; child; cognition; cognitive behavioral therapy; complication; disorientation; exercise; family history; habit; heart arrhythmia; heart infarction; high school; human; hypoplastic left heart syndrome; infancy; interview; major depression; male; mental health; music; New York Heart Association class; outpatient; palliative therapy; psychiatry; remission; risk assessment; self care; self report; sleep; systolic heart failure; time management; young adult; serotonin uptake inhibitor

Hyperdense basilar artery identified on unenhanced head CT in three cases of pediatric basilar artery occlusion - Potter, J.K.; Clemente, J.D.; Asimos, A.W. (American Journal of Emergency Medicine, 2021)
Keywords: warfarin; artery occlusion; article; ataxia; attention deficit disorder; basilar artery; brain ischemia; case report; child; clinical article; computed tomographic angiography; confusion; cranial nerve paralysis; craniectomy; diagnostic imaging; dizziness; endotracheal intubation; fever; Fontan procedure; headache; hemiparesis; human; incidence; lethargy; male; mechanical thrombectomy; mental health; nausea; nuclear magnetic resonance imaging; pediatric basilar artery occlusion; physical examination; priority journal; pulmonary valve atresia; symptomatology; thrombectomy; vomiting; x-ray computed tomography

Dobutamine stress testing for the evaluation of atrial and diastolic ventricular function in Fontan patients - Van Der Ven, J.P.G.; Bossers, S.S.M.; Van Den Bosch, E.; Dam, N.; Kuipers, I.M.; Van Iperen, G.G.; Kroft, L.J.M.; Kapusta, L.; Ten Harkel, A.D.J.; Helbing, W.A. (Open Heart, 2021)
Objective To assess the atrial and ventricular diastolic function response to dobutamine stress in Fontan patients, and to relate these measurements to exercise capacity and events during the follow-up. Methods We performed a secondary analysis of a cross-sectional multicentre study of Fontan patients with intra-atrial lateral tunnel (ILT) or extracardiac conduit (ECC) modification. Subjects underwent cardiac MRI during rest and low-dose dobutamine stress, and cardiopulmonary exercise testing. Atrial and diastolic ventricular function parameters were derived from volume-time curves. Medical records were abstracted for a composite end-point of death, listing for transplant, arrhythmia and reintervention. Spearman's r correlation tests and Cox proportional hazards models were used to assess the relation between the dobutamine response for atrial and diastolic ventricular function and outcomes, including exercise capacity. Results We included 57 patients (26 ECC; 31 ILT) aged 12.8 (IQR (10.3-15.5)) years. During dobutamine stress atrial cyclic volume change increased (3.0 (0.4-5.9) mL/m 2, p<0.001), as did early (1.9 (-1.6 to 3.6) mL/m 2, p=0.001) and late emptying volume (2.2 (0.2-4.4) mL/m 2, p<0.001). Ventricular early filling decreased (-1.6 (-5.7 to 0.7) mL/m 2,p=0.046) and ventricular late filling increased (1.0 (-0.4 to 3.4) mL/m 2,p<0.001) while stroke volume remained similar. Only for patients with the ECC modification, atrial early emptying volume increase correlated with peak oxygen uptake (ρ=0.66,p=0.002). No other parameter related to exercise capacity. During a median 7.1-year follow-up, 22 patients reached the composite endpoint. No parameter predicted events during the follow-up. Conclusions Dobutamine stress augmented atrial reservoir and pump function for Fontan patients. Atrial early emptying reserve related to exercise capacity in ECC patients. No other atrial or diastolic ventricular function parameter related to outcomes.
Keywords: article; cardiovascular magnetic resonance; child; congenital heart malformation; controlled study; exercise test; female; follow up; Fontan procedure; heart arrhythmia; heart atrium; heart stroke volume; heart ventricle function; human; low drug dose; major clinical study; male; medical record; multicenter study; peak oxygen uptake; school child; secondary analysis; surgery; transplantation; dobutamine

Birth defects and unconventional natural gas developments in Texas, 1999–2011 - Tang, I.W.; Langlois, P.H.; Vieira, V.M. (Environmental Research, 2021)
Unconventional natural gas developments (UNGD) may release air and water pollutants into the environment, potentially increasing the risk of birth defects. We conducted a case-control study evaluating 52,955 cases with birth defects and 642,399 controls born between 1999 and 2011 to investigate the relationship between UNGD exposure and the risk of gastroschisis, congenital heart defects (CHD), neural tube defects (NTDs), and orofacial clefts in Texas. We calculated UNGD densities (number of UNGDs per area) within 1, 3, and 7.5 km of maternal address at birth and categorized exposure by density tertiles. For CHD subtypes with large case numbers, we also performed time-stratified analyses to examine temporal trends. We calculated adjusted odds ratios (aOR) and 95% confidence intervals (CI) for the association with UNGD exposure, accounting for maternal characteristics and neighborhood factors. We also included a bivariable smooth of geocoded maternal location in an additive model to account for unmeasured spatially varying risk factors. Positive associations were observed between the highest tertile of UNGD density within 1 km of maternal address and risk of anencephaly (aOR: 2.44, 95% CI: 1.55, 3.86), spina bifida (aOR: 2.09, 95% CI: 1.47, 2.99), gastroschisis among older mothers (aOR: 3.19, 95% CI: 1.77, 5.73), aortic valve stenosis (aOR: 1.90, 95% CI: 1.33, 2.71), hypoplastic left heart syndrome (aOR: 2.00, 95% CI: 1.39, 2.86), and pulmonary valve atresia or stenosis (aOR: 1.36, 95% CI: 1.10, 1.66). For CHD subtypes, results did not differ substantially by distance from maternal address or when residual confounding was considered, except for atrial septal defects. We did not observe associations with orofacial clefts. Our results suggest that UNGDs were associated with some CHDs and possibly NTDs. In addition, we identified temporal trends and observed presence of spatial residual confounding for some CHDs.
Keywords: natural gas; adolescent; adult; anencephalus; aortic valve stenosis; case control study; child; cleft lip; cleft lip with or without cleft palate; cleft palate; congenital heart malformation; congenital malformation; controlled study; endocardial cushion defect; Fallot tetralogy; female; gastroschisis; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; Hispanic; household income; human; hypoplastic left heart syndrome; major clinical study; male; maternal age; maternal exposure; maternal smoking; maternal stress; maternal welfare; neural tube defect; newborn; pregnancy outcome; prenatal exposure; priority journal; pulmonary valve atresia; pulmonary valve stenosis; rural area; rural population; social status; spinal dysraphism; Texas; tricuspid valve atresia; urban population; water pollutant

Percutaneous pulmonary artery debanding - Tomita, H.; Fujii, T.; Kise, H.; Oyama, N.; Shimizu, T.; Nagaoka, K.; Tarui, S.; Miyahara, Y.; Ishino, K. (Journal of Cardiology, 2021)
Background: There is a paucity of data on palliative or total percutaneous pulmonary artery debanding (p-debanding), particularly with use of a stent. Methods: Twelve p-debandings in eight patients were included in this study. Age at pulmonary artery banding (PAB) ranged from 3 days to 1 year (median, 13 days), while p-debanding was performed at 2–157 (7) months. The body weight at the p-debanding ranged from 3.2 to 22.2 (7.3) kg. We chose the balloon diameter of 30–50% to the circumference of the band for palliative, and larger than 50% for total p-debanding, respectively. In either way, the balloon diameter did not exceed 1.5 times the reference vessel diameter. Stent was implanted for palliative p-debanding in 2 patients. Results: 1. The circumference of the band ranged from 16 to 23 (20) mm, while the balloon diameter ranged from 20–60 (40)% to that, where larger than 50% was used for 2 procedures intended total p-debanding. 2. PAB diameter increased from 2.5–4.7 (3.0) mm to 2.8–9.5 (4.5) mm (p < 0.01), however, there was no significant change in the diameter in 2 procedures. In one patient, p-debanding was the definitive treatment associated with spontaneous near closure of muscular ventricular septal defect, in another patient of congenitally corrected transposition of the great arteries, severely depressed left ventricular ejection fraction was recovered following p-debanding. 3. Arterial oxygen saturation (SaO2) increased from 64–97 (80)% to 66–95 (90)% (p < 0.01), while in 10 procedures of 6 patients where the indication of p-debanding was hypoxia, SaO2 increased in 8 procedures. There was no significant pulmonary hypertension following p-debanding. Conclusion: Palliative or total p-debanding using balloon and/or stenting is generally feasible and effective. A balloon diameter 35–50% to the band circumference in palliative, and more than 50% in total p-debanding, while in either way less than 1.5 times the reference vessel diameter, is safe.
Keywords: balloon catheter; polytetrafluoroethylene; arterial oxygen saturation; article; balloon dilatation; body weight; child; chromosome aberration; clinical article; congenitally corrected transposition of the great arteries; controlled study; female; heart left ventricle ejection fraction; heart left ventricle failure; heart single ventricle; heart ventricle septum defect; human; infant; lung artery banding; lung artery pressure; male; newborn; observational study; percutaneous pulmonary artery debanding; pulmonary hypertension; pulmonary valve stenosis; retrospective study

Fetal Umbilical Arterial Pulsatility Correlates With 2-Year Growth and Neurodevelopmental Outcomes in Congenital Heart Disease - Abeysekera, J.B.; Gyenes, D.L.; Atallah, J.; Robertson, C.M.T.; Bond, G.Y.; Rebeyka, I.M.; Moez, E.K.; Dinu, I.A.; Switzer, H.N.; Hornberger, L.K. (Canadian Journal of Cardiology, 2021)
Background: Children with congenital heart disease (CHD) are at risk of adverse long-term neurodevelopmental outcomes, believed to be, in part, secondary to prenatal insults. Placental pathology and altered fetal middle cerebral arterial (MCA) flow suggestive of brain sparing have been documented in fetal CHD. In the present study we investigated the relationship between MCA and umbilical arterial (UA) flow patterns in fetal transposition of the great arteries (d-TGA) and hypoplastic left heart syndrome (HLHS) and growth and 2-year neurodevelopmental outcomes. Methods: We included children with d-TGA and HLHS who had third-trimester fetal echocardiograms between 2004 and 2014, at which time umbilical artery (UA) and MCA pulsatility indices (PIs) were measured, and who underwent 2-year growth and neurodevelopmental assessments. Results: We identified 24 children with d-TGA and 36 with HLHS. Mean age at fetal echocardiography was 33.8 ± 3.5 weeks. At 2-year follow-up, head circumference z score (standard deviation [SD]) was –0.09 (1.07) and 0.17 (1.7) for the d-TGA and HLHS groups, respectively. Bayley III mean (SD) cognitive, language, and motor scores were 97.7 (10.8), 94.7 (13.4), and 98.6 (8.6) for the d-TGA group and 90.3 (13.9), 87.2 (17.5), and 85.3 (16.2) for the HLHS group. On multivariate linear regression analysis, UA-PI was associated (effect sizes [95% CI]) with length (–1.45 [–2.7, –0.17], P = 0.027), weight (–1.46 [–2.6 to –0.30], P = 0.015) and cognitive scores (–14.86 [–29.95 to 0.23], P = 0.05) at 2 years of age. MCA PI showed no statistically significant correlation. Conclusions: In fetal d-TGA and HLHS, a higher UA-PI in the third trimester, suggestive of placental insufficiency—but not MCA-PI—is associated with worse 2-year growth and neurodevelopment.
Keywords: adult; artery blood flow; article; Bayley Scales of Infant Development; child; clinical article; controlled study; echocardiography; effect size; female; fetus; follow up; great vessels transposition; head circumference; human; hypoplastic left heart syndrome; language; linear regression analysis; nervous system development; placenta insufficiency; preschool child; pulse wave; third trimester pregnancy; umbilical artery

Family Function, Quality of Life, and Well-Being in Parents of Infants With Hypoplastic Left Heart Syndrome - Mussatto, K.A.; Van Rompay, M.I.; Trachtenberg, F.L.; Pemberton, V.; Young-Borkowski, L.; Uzark, K.; Hollenbeck-Pringle, D.; Dunbar-Masterson, C.; Infinger, P.; Walter, P.; Sawin, K. (Journal of family nursing, 2021)
Survival for hypoplastic left heart syndrome (HLHS) has improved dramatically. Little is known about early family function, quality of life (QOL), or well-being/adjustment for parents of infants with HLHS. Parent/family outcomes over time, predictors, and differences in 143 mothers and 72 fathers were examined. Parents reported better family function compared with published norms, but 26% experienced family dysfunction. QOL and well-being were significantly lower than adult norms. QOL scores generally declined over time, whereas self-reported well-being improved. Responses from mothers and fathers showed different trends, with mothers having worse scores on most measures and at most time points. Being a single parent was a risk factor for poorer family function, but not for lower individual QOL or well-being. Family characteristics, stress, and coping skills were predictive of outcomes. Parents' psychosocial responses to the challenges of life with infants with HLHS change over time. Individually tailored psychosocial support is needed.
Keywords: adult; article; controlled study; coping behavior; family size; father; female; human; hypoplastic left heart syndrome; infant; male; physiological stress; psychosocial care; quality of life; risk factor; single parent; wellbeing

Adult Congenital Heart Disease Survivors at Age 50 Years: Medical and Psychosocial Status - Rehan, R.; Kotchetkova, I.; Cordina, R.; Celermajer, D. (Heart Lung and Circulation, 2021)
Background: Although advances in congenital heart disease (CHD) management have allowed survival of children with even highly complex CHD lesions well into adult life, the burden of disease (medical, psychological and social) has not been well characterised, for those living to middle age and beyond. Methods: We assessed 121 consecutive patients from our adult CHD centre, who survived to age 50 years and who had had moderate or complex CHD lesions. Pre-specified groups included those with repaired tetralogy of Fallot (TOF) (n=56), coarctation of the aorta (CoA) (n=34), systemic right ventricle (RV) (n=9), Fontan surgery for “single ventricle” hearts (n=5), those with repaired Ebstein's Anomaly (n=9) and other complex CHD (n=8). Results: The overall burden of disease was very substantial. Of the TOF patients, almost half (46%) had required at least one open-heart reoperation and 41% had had a pacemaker or implantable defibrillator; 20% had had a radiofrequency ablation and 32% were on anti-arrhythmic therapy. Over 40% had ≥1 admission for heart failure and 9% had had endocarditis. Only 64% were still employed. Of the CoA survivors, 50% had had a second operation (aortic valve and/or descending aortic surgery), 88% were on medications for hypertension and 62% were still employed. In the more complex groups, approximately half had been diagnosed with depression/anxiety and cerebrovascular event, heart failure and/or significant arrhythmias were common. Conclusions: Despite considerable advances, adults with CHD who survive to age 50 years have experienced high levels of physical and mental health complications.
Keywords: adult; anxiety; aortic coarctation; aortic valve; article; cerebrovascular disease; complication; congenital heart disease; controlled study; depression; descending aortic surgery; disease burden; drug therapy; Ebstein anomaly; endocarditis; Fallot tetralogy; female; heart arrhythmia; heart right ventricle; heart single ventricle; human; hypertension; implantable cardioverter defibrillator; major clinical study; male; mental health; radiofrequency ablation; reoperation; surgery; survivor; antiarrhythmic agent

Intraperitoneal corticosteroids for recurrent ascites in patients with Fontan circulation: Initial clinical experience - Wu, F.M.; Valente, A.M.; Nigrovic, P.A.; Rutherford, A.E.; Singh, M.N. (Journal of Cardiac Surgery, 2021)
Individuals with single-ventricle congenital heart disease who are palliated to a Fontan circulation are at risk for heart failure and liver disease, with recurrent ascites being a potentially debilitating cause of late morbidity. Although ascites associated with heart failure or liver failure is usually characterized by a high serum-ascites albumin gradient (SAAG), we have observed multiple instances of ascites in Fontan patients with low SAAG, suggesting an inflammatory process. We present three cases in which recalcitrant ascites severely and adversely impacted the quality of life and describe our initial experience with intraperitoneal corticosteroids in this setting.
Keywords: C reactive protein; diuretic agent; fresh frozen plasma; hydrocortisone; methotrexate; prednisone; triamcinolone acetonide; triamcinolone hexacetonide; adolescent; adrenal insufficiency; adult; article; ascites; atriopulmonary connection; cardiac index; case report; child; clinical article; computer assisted tomography; corticotropin test; drug dose escalation; erythrocyte transfusion; female; Fontan procedure; heart arrhythmia; heart atrium arrhythmia; heart catheterization; heart right ventricle double outlet; hemoperitoneum; human; human tissue; hyperglycemia; liver biopsy; liver cirrhosis; liver fibrosis; low drug dose; middle aged; mitral valve atresia; paracentesis; peritoneal biopsy; peritonitis; plasma transfusion; preschool child; protein blood level; pulmonary valve atresia; quality of life; radiofrequency ablation; recurrent ascites; recurrent disease; sudden death; traffic accident; young adult

Trajectories in Neurodevelopmental, Health-Related Quality of Life, and Functional Status Outcomes by Socioeconomic Status and Maternal Education in Children with Single Ventricle Heart Disease - Bucholz, E.M.; Sleeper, L.A.; Sananes, R.; Brosig, C.L.; Goldberg, C.S.; Pasquali, S.K.; Newburger, J.W. (Journal of Pediatrics, 2021)
Trajectories of neurodevelopment and quality of life were analyzed in children with hypoplastic left heart syndrome according to socioeconomic status (SES) and maternal education. Lower SES and less maternal education were associated with greater early delays in communication and problem-solving and progressive delays in problem-solving and fine motor skills over time.
Keywords: article; behavior; Blalock Taussig shunt; child; controlled study; educational status; female; follow up; functional status; functional status assessment; head circumference; heart single ventricle; human; hypoplastic left heart syndrome; interpersonal communication; major clinical study; male; maternal attitude; nerve cell differentiation; nervous system development; newborn; Norwood procedure; patient-reported outcome; pediatric patient; Pediatric Quality of Life Inventory; priority journal; problem solving; quality of life; right ventricle to pulmonary artery conduit; social interaction; social psychology; social status

Reduced hippocampal volumes and memory deficits in adolescents with single ventricle heart disease - Pike, N.A.; Roy, B.; Moye, S.; Cabrera-Mino, C.; Woo, M.A.; Halnon, N.J.; Lewis, A.B.; Kumar, R. (Brain and Behavior, 2021)
Introduction: Adolescents with single ventricle congenital heart disease (SVHD) show functional deficits, particularly in memory and mood regulation. Hippocampi are key brain structures that regulate mood and memory; however, their tissue integrity in SVHD is unclear. Our study aim is to evaluate hippocampal volumes and their associations with memory, anxiety, and mood scores in adolescents with SVHD compared to healthy controls. Methods: We collected brain magnetic resonance imaging data from 25 SVHD (age 15.9 ± 1.2 years; 15 male) and 38 controls (16.0 ± 1.1 years; 19 male) and assessed memory (Wide Range Assessment of Memory and Learning 2, WRAML2), anxiety (Beck Anxiety Inventory, BAI), and mood (Patient Health Questionnaire 9, PHQ-9) functions. Both left and right hippocampi were outlined and global volumes, as well as three-dimensional surfaces were compared between groups using ANCOVA and associations with cognitive and behavioral scores with partial correlations (covariates: age and total brain volume). Results: The SVHD group showed significantly higher BAI (p =.001) and PHQ-9 (p <.001) scores, indicating anxiety and depression symptoms and significantly reduced WRAML2 scores (p <.001), suggesting memory deficits compared with controls. SVHD group had significantly reduced right global hippocampal volumes (p =.036) compared with controls, but not the left (p =.114). Right hippocampal volume reductions were localized in the CA1, CA4, subiculum, and dentate gyrus. Positive correlations emerged between WRAML2 scores and left (r = 0.32, p =.01) and right (r = 0.28, p =.03) hippocampal volumes, but BAI and PHQ-9 did not show significant correlations. Conclusion: Adolescents with SVHD show reduced hippocampal volumes, localized in several sites (CA1, CA4, subiculum, and dentate gyrus), which are associated with memory deficits. The findings indicate the need to explore ways to improve memory to optimize academic achievement and ability for self-care in the condition.
Keywords: nuclear magnetic resonance scanner; adolescent; adult; amygdala; anxiety; article; Beck Anxiety Inventory; brain size; cerebrospinal fluid; cognition assessment; congenital heart disease; controlled study; dentate hilus; depression; female; Fourier transform; heart single ventricle; heart ventricle; hippocampus; human; image analysis; image segmentation; learning; major clinical study; male; memory assessment; Montreal cognitive assessment; nuclear magnetic resonance imaging; oxygen saturation; Patient Health Questionnaire 9; pterygoid muscle; visual memory; working memory

Mental health disorders in children with congenital heart disease - Gonzalez, V.J.; Kimbro, R.T.; Cutitta, K.E.; Shabosky, J.C.; Bilal, M.F.; Penny, D.J.; Lopez, K.N. (Pediatrics, 2021)
BACKGROUND: Data on anxiety, depression, and attention-deficit/hyperactivity disorder (ADHD) are lacking for youth with congenital heart disease (CHD), particularly those with simple CHD. This study aims to characterize these disorders in youth with CHD compared to those without CHD. METHODS: A comparative cross-sectional study was conducted by using the electronic medical records of a large tertiary care hospital between 2011 and 2016. Inclusion criteria were youth aged 4 to 17 years with.1 hospitalization or emergency department visits. Exclusion criteria were patients with arrhythmias or treatment with clonidine and/or benzodiazepines. The primary predictor variable was CHD type: simple, complex nonsingle ventricle, and complex single ventricle. The primary outcome variable was a diagnosis and/or medication for anxiety and/or depression or ADHD. Data were analyzed by using logistic regression (Stata v15; Stata Corp, College Station, TX). RESULTS: We identified 118 785 patients, 1164 with CHD. Overall, 18.2% (n = 212) of patients with CHD had a diagnosis or medication for anxiety or depression, compared with 5.2% (n = 6088) of those without CHD. All youth with CHD had significantly higher odds of anxiety and/ or depression or ADHD. Children aged 4 to 9 years with simple CHD had ∼5 times higher odds (odds ratio: 5.23; 95% confidence interval: 3.87-7.07) and those with complex single ventricle CHD had ∼7 times higher odds (odds ratio: 7.46; 95% confidence interval: 3.70-15.07) of diagnosis or treatment for anxiety and/or depression. Minority and uninsured youth were significantly less likely to be diagnosed or treated for anxiety and/or depression or ADHD, regardless of disease severity. CONCLUSIONS: Youth with CHD of all severities have significantly higher odds of anxiety and/or depression and ADHD compared to those without CHD. Screening for these conditions should be considered in all patients with CHD.
Keywords: adolescent; anxiety; article; attention deficit disorder; child; controlled study; cross-sectional study; depression; drug combination; drug therapy; electronic medical record; emergency ward; female; heart arrhythmia; heart single ventricle; hospitalization; human; juvenile; major clinical study; male; medically uninsured; outcome assessment; outcome variable; predictor variable; tertiary care center; benzodiazepine derivative; clonidine

Six-year neurodevelopmental outcomes for children with single-ventricle physiology - Sananes, R.; Goldberg, C.S.; Newburger, J.W.; Hu, C.; Trachtenberg, F.; Gaynor, J.W.; Mahle, W.T.; Miller, T.; Uzark, K.; Mussatto, K.A.; Pizarro, C.; Jacobs, J.P.; et al. (Pediatrics, 2021)
OBJECTIVES: To determine if neurodevelopmental deficits in children with single-ventricle abstract physiology change with age and early developmental scores predict 6-year outcomes. METHODS: In the Single Ventricle Reconstruction Trial, Bayley Scales of Infant Development, Second Edition, were administered at 14 months of age, and parents completed the Behavior Assessment System for Children, Second Edition (BASC-2) annually from the ages of 2 to 6 years. Scores were classified as average, at risk, or impaired. We calculated sensitivities, specificities, and positive and negative predictive values of earlier tests on 6-year outcomes. RESULTS: Of 291 eligible participants, 244 (84%) completed the BASC-2 at 6 years; more Single Ventricle Reconstruction participants than expected on the basis of normative data scored at risk or impaired on the BASC-2 Adaptive Skills Index at that evaluation (28.7% vs 15.9%; P,.001). Children with Adaptive Skills Composite scores,2 SD below the mean at the age of 6 were more likely to have had delayed development at 14 months, particularly on the Psychomotor Development Index (sensitivity of 79%). However, the positive predictive value of the 14-month Mental Development Index and Psychomotor Development Index for 6-year BASC-2 Adaptive Scores was low (44% and 36%, respectively). Adaptive Skills Composite score impairments at the age of 6 were poorly predicted by using earlier BASC-2 assessments, with low sensitivities at the ages of 3 (37%), 4 (48%), and 5 years (55%). CONCLUSIONS: Many children with hypoplastic left heart syndrome who have low adaptive skills at the age of 6 years will not be identified by screening at earlier ages. With our findings, we highlight the importance of serial evaluations for children with critical congenital heart disease throughout development.
Keywords: article; Bayley Scales of Infant Development; behavior assessment; child; controlled study; diagnostic test accuracy study; female; heart single ventricle; human; hypoplastic left heart syndrome; infant; major clinical study; male; predictive value; preschool child; psychomotor development; sensitivity and specificity; skill; surgery

Congenital atresia of the left main coronary artery with left ventricular noncompaction: From infancy to adulthood - Qiu, Y.G.; Zheng, J.Y.; Han, L.; Ding, W.H.; Li, T.C.; Zhao, J.H. (Anatolian Journal of Cardiology, 2021)
Keywords: beta adrenergic receptor blocking agent; adult; artery occlusion; article; atresia; cardiovascular magnetic resonance; case report; child; claustrophobia; clinical article; collateral artery; computed tomographic angiography; congenital heart disease; congestive cardiomyopathy; coronary angiography; dyspnea; echocardiography; electrocardiogram; female; heart failure; heart left ventricle ejection fraction; heart muscle fibrosis; human; hypoplastic left heart syndrome; male; mitral valve regurgitation; Q wave; ST segment depression; systolic heart murmur; tissue Doppler imaging; ventricular noncompaction

Outcomes of Preterm Infants With Congenital Heart Defects After Early Surgery: Defining Risk Factors at Different Time Points During Hospitalization - Cheung, P.-Y.; Hajihosseini, M.; Dinu, I.A.; Switzer, H.; Joffe, A.R.; Bond, G.Y.; Robertson, C.M.T. (Frontiers in Pediatrics, 2020)
Background: Compared with those born at term gestation, infants with complex congenital heart defects (CCHD) who were delivered before 37 weeks gestational age and received neonatal open-heart surgery (OHS) have poorer neurodevelopmental outcomes in early childhood. We aimed to describe the growth, disability, functional, and neurodevelopmental outcomes in early childhood of preterm infants with CCHD after neonatal OHS. Prediction models were evaluated at various timepoints during hospitalization which could be useful in the management of these infants. Study Design: We studied all preterm infants with CCHD who received OHS within 6 weeks of corrected age between 1996 and 2016. The Western Canadian Complex Pediatric Therapies Follow-up Program completed multidisciplinary comprehensive neurodevelopmental assessments at 2-year corrected age at the referral-site follow-up clinics. We collected demographic and acute-care clinical data, standardized age-appropriate outcome measures including physical growth with calculated z-scores; disabilities including cerebral palsy, visual impairment, permanent hearing loss; adaptive function (Adaptive Behavior Assessment System-II); and cognitive, language, and motor skills (Bayley Scales of Infant and Toddler Development-III). Multiple variable logistic or linear regressions determined predictors displayed as Odds Ratio (OR) or Effect Size (ES) with 95% confidence intervals. Results: Of 115 preterm infants (34 ± 2 weeks gestation, 2,339 ± 637 g, 64% males) with CCHD and OHS, there were 11(10%) deaths before first discharge and 21(18%) deaths by 2-years. Seven (6%) neonates had cerebral injuries, 7 had necrotizing enterocolitis; none had retinopathy of prematurity. Among 94 survivors, 9% had cerebral palsy and 6% had permanent hearing loss, with worse outcomes in those with syndromic diagnoses. Significant predictors of mortality included birth weight z-score [OR 0.28(0.11,0.72), P = 0.008], single-ventricle anatomy [OR 5.92(1.31,26.80), P = 0.021], post-operative ventilation days [OR 1.06(1.02,1.09), P = 0.007], and cardiopulmonary resuscitation [OR 11.58 (1.97,68.24), P = 0.007]; for adverse functional outcome in those without syndromic diagnoses, birth weight 2,000–2,499 g [ES −11.60(−18.67, −4.53), P = 0.002], post-conceptual age [ES −0.11(−0.22,0.00), P = 0.044], post-operative lowest pH [ES 6.75(1.25,12.25), P = 0.017], and sepsis [ES −9.70(−17.74, −1.66), P = 0.050]. Conclusions: Our findings suggest preterm neonates with CCHD and early OHS had significant mortality and morbidity at 2-years and were at risk for cerebral palsy and adverse neurodevelopment. This information may be important for management, parental counseling and the decision-making process.
Keywords: adaptive behavior; article; artificial ventilation; Bayley Scales of Infant Development; birth weight; brain injury; cerebral palsy; child; childhood; controlled study; counseling; decision making; demography; effect size; emergency care; female; follow up; hearing impairment; heart single ventricle; hospitalization; human; infant; language; linear regression analysis; major clinical study; male; morbidity; mortality; motor performance; necrotizing enterocolitis; nervous system development; newborn; open heart surgery; patient referral; prediction; pregnancy; resuscitation; retrolental fibroplasia; risk factor; sepsis; surgery; survivor; visual impairment

Parent and physician understanding of prognosis in hospitalized children with advanced heart disease - Morell, E.; Miller, M.K.; Lu, M.; Friedman, K.G.; Breitbart, R.E.; Reichman, J.R.; McDermott, J.; Sleeper, L.A.; Blume, E.D. (Journal of the American Heart Association, 2021)
BACKGROUND: The unpredictable trajectory of pediatric advanced heart disease makes prognostication difficult for physicians and informed decision-making challenging for families. This study evaluated parent and physician understanding of disease burden and prognosis in hospitalized children with advanced heart disease. METHODS AND RESULTS: A longitudinal survey study of parents and physicians caring for patients with advanced heart disease age 30 days to 19 years admitted for >7 days was performed over a 1-year period (n=160 pairs). Percentage agreement and weighted kappa statistics were used to assess agreement. Median patient age was 1 year (interquartile range, 1-5), 39% had single-ventricle lesions, and 37% were in the cardiac intensive care unit. Although 92% of parents reported understanding their childs prognosis extremely well or well, 28% of physicians thought parents understood the prognosis only a little, somewhat, or not at all. Better parent-reported prognostic understanding was associated with greater preparedness for their childs medical problems (odds ratio, 4.7; 95% CI, 1.4-21.7, P=0.02). There was poor parent-physician agreement in assessing functional class, symptom burden, and likelihood of limitations in physical activity and learning/behavior; on average, parents were more optimistic. Many parents (47%) but few physicians (6%) expected the child to have normal life expectancy. CONCLUSIONS: Parents and physicians caring for children with advanced heart disease differed in their perspectives regarding prognosis and disease burden. Physicians tended to underestimate the degree of parent-reported symptom burden. Parents were less likely to expect limitations in physical activity, learning/behavior, and life expectancy. Combined interventions involving patient-reported outcomes, parent education, and physician communication tools may be beneficial.
Keywords: adult; article; care behavior; child; congenital heart disease; controlled study; coronary care unit; disease burden; female; heart single ventricle; hospitalized child; human; infant; kappa statistics; learning; life expectancy; major clinical study; male; outcome assessment; patient-reported outcome; pediatrics; physical activity; prognosis; young adult

Prevalence of structural birth defects among infants with Down syndrome, 2013–2017: A US population-based study - Heinke, D.; Isenburg, J.L.; Stallings, E.B.; Short, T.D.; Le, M.; Fisher, S.; Shan, X.; Kirby, R.S.; Nguyen, H.H.; Nestoridi, E.; Nembhard, W.N.; Romitti, P.A.; et al. (Birth Defects Research, 2021)
Background: Down syndrome is the most common chromosomal disorder at birth and is often accompanied by structural birth defects. Current data on major structural defects in this population are limited. Methods: States and territorial population-based surveillance programs submitted data on identified cases of Down syndrome and identified structural birth defects during 2013–2017. We estimated prevalence by program type and maternal and infant characteristics. Among programs with active case ascertainment, we estimated the prevalence of birth defects by organ system and for specific defects by maternal age (<35, ≥35) and infant sex. Results: We identified 13,376 cases of Down syndrome. Prevalence among all programs was 12.7 per 10,000 live births. Among these children, 75% had at least one reported co-occurring birth defect diagnosis code. Among 6,210 cases identified by active programs, 66% had a cardiovascular defect with septal defects being the most common: atrial (32.5%), ventricular (20.6%), and atrioventricular (17.4%). Defect prevalence differed by infant sex more frequently than by maternal age. For example, atrioventricular septal defects were more common in female children (20.1% vs. 15.1%) while limb deficiencies were more prevalent in male children (0.4% vs. 0.1%). Conclusions: Our study provides updated prevalence estimates for structural defects, including rare defects, among children with Down syndrome using one of the largest and most recent cohorts to date. These data may aid clinical care and surveillance.
Keywords: anophthalmia; aortic arch interruption; aortic coarctation; aortic valve stenosis; arterial trunk; article; atrioventricular septal defect; bile duct atresia; bladder exstrophy; child; choana atresia; cleft lip; cleft lip palate; cleft palate; congenital cataract; congenital malformation; craniofacial synostosis; diaphragm hernia; Down syndrome; Ebstein anomaly; encephalocele; esophagus atresia; Fallot tetralogy; gastroschisis; gestational age; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart septum defect; holoprosencephaly; human; hypoplastic left heart syndrome; hypospadias; ICD-10-CM; ICD-9-CM; intestine atresia; kidney agenesis; limb defect; lung vein drainage anomaly; maternal age; microphthalmia; microtia; omphalocele; pregnancy outcome; prevalence; pulmonary valve atresia; risk factor; spinal dysraphism; stenosis; tracheoesophageal fistula; tricuspid valve atresia; trisomy 13; trisomy 18; trisomy 21; Turner syndrome

A rare case report of renal vein pseudoaneurysm after blunt trauma - Mun, Y.S.; Sung, W.Y. (Medicine, 2021)
RATIONALE: Renal vein pseudoaneurysm after blunt trauma is an extremely rare clinical disease. Different interventions, such as conservative, surgical, and endovascular treatments, can be considered. However, previous studies have not described the optimal treatment strategies for this condition. Furthermore, there is a significant lack of prior case reports and of standardized treatment guidelines for trauma-induced renal vein pseudoaneurysm patients who previously maintained antithrombotic agent. PATIENT CONCERNS: A 23-year-old female patient visited the emergency department after sustaining blunt injury caused by falling. The patient was diagnosed with multiple limb and rib fractures. A right renal vein pseudoaneurysm was found on abdominal computed tomography scan. Initially, there was no other organ damage, and the patient was hemodynamically stable. Thus, nonsurgical, conservative management was considered. However, the patient's hematocrit and hemoglobin levels decreased, and there was no hemodynamic improvement. The patient required lifelong treatment with aspirin because she previously underwent Fontan surgery, and orthopedic surgery for multiple fractures was planned. Thus, considering these factors, the treatment method was changed from conservative management to endovascular stent insertion. DIAGNOSES: Abdominal computed tomography and renal venography revealed a right renal vein pseudoaneurysm. INTERVENTIONS: On the basis of the abdominal computed tomography scan and renal venography findings, the endovascular stent graft was inserted across the pseudoaneurysm area. OUTCOMES: Upon placement of the endovascular stent, hemoglobin and hematocrit levels gradually returned to normal. The patient's vital signs and general condition had improved. The patient recovered without any complications and was discharged 29 days after hospitalization. LESSONS: Some patients with traumatic renal vein pseudoaneurysm do not experience hemodynamic improvement despite conservative treatment. Hence, endovascular procedure may be considered for these patients, particularly those who require antithrombotic treatment for a previous disease.
Keywords: blunt trauma; case report; complication; false aneurysm; female; human; kidney vein; young adult

Associations between blood biomarkers, cardiac function, and adverse outcome in a young fontan cohort - van den Bosch, E.; Bossers, S.S.M.; Kamphuis, V.P.; Boersma, E.; Roos-Hesselink, J.W.; Breur, J.M.P.J.; Ten Harkel, A.D.J.; Kapusta, L.; Bartelds, B.; Roest, A.A.W.; Kuipers, I.M.; Blom, N.A.; et al. (Journal of the American Heart Association, 2021)
BACKGROUND: Patients who have undergone the Fontan procedure are at high risk of circulatory failure. In an exploratory analysis we aimed to determine the prognostic value of blood biomarkers in a young cohort who have undergone the Fontan procedure. METHODS AND RESULTS: In multicenter prospective studies patients who have undergone the Fontan procedure underwent blood sampling, cardiopulmonary exercise testing, and stress cardiac magnetic resonance imaging. Several biomarkers including NT-proBNP (N-terminal pro-B-type natriuretic peptide), GDF-15 (growth differentiation factor 15), Gal-3 (galectin-3), ST2 (suppression of tumorigenicity 2), DLK-1 (protein delta homolog 1), FABP-4 (fatty acid-binding protein 4), IGFBP-1 (insulin-like growth factor-binding protein 1), IGFBP-7, MMP-2 (matrix metalloproteinase 2), and vWF (von Willebrand factor) were assessed in blood at 9.6 (7.1–12.1) years after Fontan completion. After this baseline study measurement, follow-up information was collected on the incidence of adverse cardiac events, including cardiac death, out of hospital cardiac arrest, heart transplantation (listing), cardiac reintervention (severe events), hospitalization, and cardioversion/ablation for arrhythmias was collected and the relation with blood biomarkers was assessed by Cox proportional hazard analyses. The correlation between biomarkers and other clinical parameters was evaluated. We included 133 patients who have undergone the Fontan procedure, median age 13.2 (25th, 75th percentile 10.4–15.9) years, median age at Fontan 3.2 (2.5–3.9) years. After a median follow-up of 6.2 (4.9–6.9) years, 36 (27.1%) patients experienced an event of whom 13 (9.8%) had a severe event. NT-proBNP was associated with (all) events during follow-up and remained predictive after correction for age, sex, and dominant ventricle (hazard ratio, 1.89; CI, 1.32–2.68). The severe event-free survival was better in patients with low levels of GDF-15 (P=0.005) and vWF (P=0.008) and high levels of DLK-1 (P=0.041). There was a positive correlation (β=0.33, P=0.003) between DLK-1 and stress cardiac magnetic resonance imaging functional reserve. CONCLUSIONS: NT-proBNP, GDF-15, vWF, DLK-1, ST-2 FABP-4, and IGFBP-7 levels relate to long-term outcome in young patients who have undergone the Fontan procedure.
Keywords: adolescent; adverse outcome; article; blood sampling; carcinogenicity; cardiovascular magnetic resonance; cardioversion; clinical assessment; congenital heart disease; controlled study; event free survival; exercise test; exploratory research; female; follow up; Fontan procedure; gene expression; heart arrhythmia; heart death; heart function; heart single ventricle; heart transplantation; hospitalization; human; incidence; major clinical study; male; multicenter study; out of hospital cardiac arrest; prospective study; protein expression; surgery; amino terminal pro brain natriuretic peptide; biological marker; endogenous compound; fatty acid binding protein 4; galectin 3; gelatinase A; growth differentiation factor 15; somatomedin binding protein 1; von Willebrand factor

Glenn surgery: A safe procedure in the path of univentricular correction - Hernández-Morales, G.; Bolio-Cerdán, A.; Ruiz-González, S.; Romero-Cárdenas, P.; Villasís-Keever, M.A. (Boletin Medico del Hospital Infantil de Mexico, 2021)
Background: This study describes 35 years of experience in a tertiary care level hospital that treats cardiac patients with univentricular heart physiology who underwent Glenn surgery. Methods: The study consisted of a retrospective analysis of patients who underwent Glenn surgery, including variables related to pre-operative, intra-operative, and post-operative morbidity and mortality. Results: From 1980 to 2015, 204 Glenn surgeries were performed. The most common heart disease was tricuspid atresia IB (19.2%). In 48.1% of the cases, the procedure was performed with antegrade flow. A bilateral Glenn procedure was performed in 12.5% of the cases and 10.3% were carried out without using a cardiopulmonary bypass pump. Reported complications included infections, bleeding, arrhythmias, chylothorax, neurological alterations, and pleural effusion. The mortality rate was 2.9%. Conclusions: Glenn surgery is a palliative surgery with good results. It significantly improves patient quality of life over a long period until a total cavopulmonary shunt is performed. The complications observed are few, and the mortality rate is low. Therefore, it is a safe surgery that should be used for univentricular congenital heart disease.
Keywords: cardiopulmonary bypass cannula; catheter; adult; article; bleeding; cardiac patient; cardiopulmonary bypass; cardiovascular infection; carotid angioplasty; catheterization; cavopulmonary connection; cerclage; child; chylothorax; congenital hypoplastic anemia; female; follow up; Glenn shunt; heart arrhythmia; heart single ventricle; heterotaxy syndrome; human; hypoplasia; intraoperative morbidity; major clinical study; male; middle aged; morbidity; mortality rate; neurologic disease; oximetry; palliative therapy; perception disorder; pleura effusion; postoperative morbidity; postoperative period; preoperative morbidity; pulmonary valve atresia; quality of life; retrospective study; stenosis; surgical mortality; survival rate; tertiary care center; tricuspid valve atresia; urinary tract infection; ventilator associated pneumonia

A Multi-Interventional Nutrition Program for Newborns with Congenital Heart Disease - O'Neal Maynord, P.; Johnson, M.; Xu, M.; Slaughter, J.C.; Killen, S.A.S. (Journal of Pediatrics, 2021)
Objective: To evaluate how outcomes changed in newborns undergoing surgery for congenital heart disease after implementation of a standardized preoperative and postoperative nutrition program. Study design: We performed a single-center cohort study of newborns who underwent cardiac surgery between September 2008 and July 2015. We evaluated growth and feeding outcomes in the 2 years of preprogram time (phase 0), in the 2 years after initiation of a postoperative feeding algorithm (phase 1), and in the 2 years following introduction of a preoperative feeding program (phase 2) using traditional statistics and quality improvement methods. Results: The study included 570 newborns with congenital heart disease. Weight-for-age z-score change from birth to hospital discharge significantly improved from phase 0 (−1.02 [IQR, −1.45 to −0.63]) to phase 1 (−0.83 [IQR, −1.25 to −0.54]; P = .006), with this improvement maintained in phase 2 (−0.89 [IQR, −1.30 to −0.56]; P = .017 across phases). Gastrostomy tube use decreased significantly (25% in phase 0 vs 12% and 14% in phases 1 and 2; P < .001) and preoperative enteral feeding increased significantly (47% and 46% in phases 0 and 1 vs 76% in phase 2; P < .001) without increases in necrotizing enterocolitis, hospital stay, or mortality. Conclusions: Introduction of a multi-interventional nutrition program was associated with improved weight gain, fewer gastrostomy tubes at hospital discharge, and increased preoperative enteral feeding without increases in necrotizing enterocolitis, hospital stay, or mortality.
Keywords: feeding tube; nasogastric tube; stomach tube; age; article; body weight; child growth; child nutrition; clinical outcome; cohort analysis; congenital heart disease; controlled study; donor milk; enteric feeding; feeding behavior; feeding difficulty; female; follow up; heart single ventricle; heart surgery; high risk infant; hospital discharge; hospital readmission; hospitalization; human; length of stay; lung blood flow; major clinical study; male; multidisciplinary team; necrotizing enterocolitis; newborn; newborn intensive care; newborn mortality; newborn surgery; patent ductus arteriosus; postoperative care; postoperative period; priority journal; stakeholder engagement; standardization; surgical mortality; total quality management

Comparison of Quantitative Versus Qualitative Assessment of Single Right Ventricular Function for the Prediction of Midterm Outcomes - Zaidi, S.J.; Ross, E.; Gandhi, R.; Li, Y.; Penk, J. (Pediatric Cardiology, 2021)
Multiple studies have shown that quantitative evaluation of right ventricular (RV) systolic function in children with hypoplastic left heart syndrome (HLHS) is associated with outcomes. However, the most widely used method is qualitative, or subjective echocardiographic evaluation. Tricuspid annular displacement (TMAD) is a quantitative method and has been shown to be associated with transplant/death in a cohort of pediatric patients with HLHS. In this study, the same echocardiograms used in the quantitative TMAD study were qualitatively evaluated to see if the assessment correlated with midterm outcomes. We hypothesized that TMAD measures would outperform qualitative measurements. A previously published retrospective study of patients with systemic right ventricle demonstrated that TMAD measurements of function prior to the Glenn procedure were associated with midterm mortality/transplant (mean TMAD 12.4% for survivors and 10.0% for non-survivors/transplant, p = 0.03). Echocardiographic images used in that study were re-evaluated using qualitative assessment of function. A score between severely depressed (0) and supra-normal (7) was assigned independently by three cardiologists. A chart review included short-term clinical outcome measures in addition to midterm mortality/transplant. Spearman correlations and logistic regression were used to estimate the associations between function scores and clinical outcomes. Function scores were measured with acceptable inter- and intra-rater reliabilities in 47 patients who had echocardiograms used in the prior analysis before their bidirectional Glenn. The mean functional score was 5.3 ± 1.32 in survivors and 5.0 ± 1.02 in non-survivors/transplant. Subjective echocardiographic scores of function were not predictive of mortality (p = 0.23). Scores were correlated with length of cardiac intensive care unit stay (Spearman’s rho = − 0.31, p = 0.04), but not post-Glenn total length of hospital stay (p = 0.4). A sub-analysis was performed for each individual operator. Only one of three operators produced scores with a significant association with mortality/transplant (p = 0.01, p = 0.25, p = 0.22, respectively). Averaged subjective measurement of function by three pediatric cardiologists in children with single right ventricle prior to the Glenn procedure was not associated with midterm outcomes. Previous work based on the same echocardiograms showed that quantitative analysis was associated with midterm outcomes. This suggests quantitative analysis may be more useful in prognostication. Future studies could confirm these results and identify which quantitative methods are most helpful.
Keywords: article; cardiologist; child; clinical article; clinical assessment; clinical outcome; cohort analysis; controlled study; coronary care unit; echocardiography; female; Glenn shunt; heart right ventricle; heart single ventricle; heart ventricle function; hospitalization; human; hypoplastic left heart syndrome; intrarater reliability; male; medical record review; mortality; prediction; quantitative analysis; retrospective study; surgery; survivor; transplantation; diamide

Long-term experience with the one-and-a-half ventricle repair for simple and complex congenital heart defects - Cabrelle, G.; Castaldi, B.; Vedovelli, L.; Gregori, D.; Vida, V.L.; Padalino, M.A. (European Journal of Cardio-thoracic Surgery, 2021)
Objectives: The one-and-a-half ventricle repair (1.5VR) is a surgical alternative to Fontan circulation or high-risk biventricular repair in patients with complex congenital heart disease (CHD) with a hypoplastic right ventricle (RV). We report our 25 years of experience to evaluate whether the degree of anatomical complexity of the CHD can affect long-term outcomes. Methods: This is a retrospective study including patients undergoing 1.5VR between 1994 and 2018. Clinical records and operative reports were reviewed. Follow-up data were collected from all survivors at the last evaluation or by phone contact. Results: Twenty-nine patients underwent 1.5VR [median age: 3.5 years, interquartile range (IQR) 0.8-7.8]. Fifteen patients had 'simple' (i.e. confined to right heart lesions) anatomical characteristics (48.3%); the median tricuspid valve annulus z-score was -3.5 (IQR -6.2 to +3.6). There were no operative deaths. The median hospital stay was 21 days (IQR 10-33), with postoperative complications in 21 patients (75.8%). At a median follow-up of 13.2 years (IQR 3.2-25.6 years; completeness 96.6%), there were 3 late deaths. There was no significant difference in survival and in freedom from adverse events between simple and complex anatomy groups. However, stress test findings showed a tendency towards a higher maximum oxygen uptake in the simple group (P = 0.055). Conclusions: The 1.5VR strategy is an effective low-risk surgical option for patients with CHD with hypoplastic RV. When it is planned from birth, late outcomes can be satisfactory. In our experience, the presence of associated major cardiac anomalies was not associated with either worse early or long-term outcomes and functional status.
Keywords: article; child; clinical article; complication; congenital heart malformation; controlled study; female; follow up; functional status; heart injury; heart right ventricle; hospitalization; human; male; maximal oxygen uptake; physiological stress; postoperative complication; preschool child; retrospective study; risk assessment; survivor; tricuspid valve

Long-term outcomes of warfarin versus aspirin after Fontan surgery - Attard, C.; Monagle, P.T.; d'Udekem, Y.; Mackay, M.T.; Briody, J.; Cordina, R.; Hassan, E.B.; Simm, P.; Rice, K.; Ignjatovic, V.; Mandelstam, S.; Munns, C.; et al. (Journal of Thoracic and Cardiovascular Surgery, 2021)
Objectives: Because of the nature of the Fontan physiology, patients are at an increased risk of thromboembolic complications. As such, warfarin or aspirin is generally prescribed lifelong for thromboprophylaxis. This study aimed to compare long-term rates of cerebrovascular injury, thrombosis, bleeding, bone mineral density, and quality of life in people living with Fontan circulation receiving warfarin compared with aspirin. Methods: This was a multicenter study of a selected cohort from the Australia and New Zealand Fontan population. Participants underwent cerebral magnetic resonance imaging to detect the presence of cerebrovascular injury (n = 84) and dual-energy X-ray absorptiometry to assess bone mineral density (n = 120). Bleeding (n = 100) and quality of life (n = 90) were assessed using validated questionnaires: Warfarin and Aspirin Bleeding assessment tool and Pediatric Quality of Life Inventory, respectively. Results: Stroke was detected in 33 participants (39%), with only 7 (6%) being clinically symptomatic. There was no association between stroke and Fontan type or thromboprophylaxis type. Microhemorrhage and white matter injury were detected in most participants (96% and 86%, respectively), regardless of thromboprophylaxis type. Bleeding rates were high in both groups; however, bleeding was more frequent in the warfarin group. Bone mineral density was reduced in our cohort compared with the general population; however, this was further attenuated in the warfarin group. Quality of life was similar between the warfarin and aspirin groups. Home international normalized ratio monitoring was associated with better quality of life scores in the warfarin group. Conclusions: Cerebrovascular injury is a frequent occurrence in the Australia and New Zealand Fontan population regardless of thromboprophylaxis type. No benefit of long-term warfarin prophylaxis could be demonstrated over aspirin; however, consideration must be given to important clinical features such as cardiac function and lung function. Furthermore, the association of reduced bone health in children receiving warfarin warrants further mechanistic studies.
Keywords: article; Australia and New Zealand; bleeding; bone density; cerebrovascular accident; child; clinical feature; cohort analysis; controlled study; dual energy X ray absorptiometry; female; heart function; heart single ventricle; human; international normalized ratio; lung function; major clinical study; male; multicenter study; nuclear magnetic resonance imaging; Pediatric Quality of Life Inventory; quality of life; questionnaire; thrombosis prevention; white matter injury; acetylsalicylic acid; warfarin

Aortic Valve Repair in Neonates - Hraska, V. (Operative Techniques in Thoracic and Cardiovascular Surgery, 2021)
Congenital aortic stenosis ranges from newborns with critical obstruction at valvar level and shock to less symptomatic neonates with gradual development of symptoms of heart failure. A team-based approach may provide the best results. Echocardiography gives essential information about the aortic valve, left-sided heart structures and associated lesions. Decision making between biventricular repair and single ventricle palliation is complex. In the case of borderline left ventricular size and function the hybrid procedure should be considered, allowing patients to recover and “declare themselves” as 1- or 2-ventricle candidates. Treatment strategies should prioritize quality of life and preservation of left ventricular function. Minimizing reintervention is an important secondary priority. Both balloon and open interventions are established and effective treatments for neonates. Reintervention rates depend on original morphology of the valve and method used. In comparison with blind ballooning, where the balloon can only tear the valve tissue, open valvuloplasty is done under direct vision and is individually tailored according to the anatomy, addressing not only commissural fusion but mixoid thickening of the cusps as well, can produce a better valve with a maximum valve orifice, without causing regurgitation. Such repair preserving function of the native valve without using artificial material allows for growth of the child, minimizing the need for intervention with excellent outcome if tricuspid geometry could be achieved.
Keywords: aortic stenosis; aortic valve repair; article; balloon dilatation; child; congenital disorder; decision making; echocardiography; geometry; heart failure; heart left ventricle function; heart left ventricle size; heart single ventricle; human; newborn; obstruction; palliative therapy; quality of life; tricuspid valve; vision

A Novel Use of Liposomal Bupivacaine in Erector Spinae Plane Block for Pediatric Congenital Cardiac Surgery - Voulgarelis, S.; Halenda, G.M.; Tanem, J.M. (Case Reports in Anesthesiology, 2021)
We describe the use of liposomal bupivacaine (Exparel) in erector spinae plane blocks for two patients undergoing pediatric cardiac surgery with cardiopulmonary bypass and one undergoing division of the compressive vascular ring. The perioperative course of all patients was remarkable for low pain and sedation scores, especially after chest tube removal. Erector spinae plane blocks are an expanding pain-control technique in both adult and pediatric cardiac surgery for postoperative analgesia. Liposomal bupivacaine offers prolonged analgesia and may be an attractive option for this indication.
Keywords: chest tube; mediastinal drainage catheter; bupivacaine; dexmedetomidine; epinephrine; milrinone; morphine; aortic stenosis; article; autism; cardiopulmonary bypass; case report; child; choana atresia; chromosome 13; chromosome deletion; clinical article; congenital heart disease; controlled study; Dandy Walker syndrome; developmental delay; Ebstein anomaly; erector spinae muscle; erector spinae plane block; female; Glenn shunt; heart right ventricle double outlet; heart surgery; heterotaxy syndrome; horseshoe kidney; human; hypertension; hypoplastic left heart syndrome; infant; liposomal delivery; male; nerve block; pediatric surgery; postoperative analgesia; pulmonary valve stenosis; school child; sedation; syndrome CHARGE; transluminal valvuloplasty; vascular ring; exparel

Education of Children With Cyanotic Congenital Heart Disease After Neonatal Cardiac Surgery - Pfitzer, C.; Buchdunger, L.A.; Helm, P.C.; Blickle, M.J.; Rosenthal, L.-M.; Ferentzi, H.; Berger, F.; Bauer, U.M.M.; Schmitt, K.R.L. (Annals of Thoracic Surgery, 2021)
Background: The aim of the study was to evaluate the educational achievement of patients diagnosed with univentricular heart physiology (UVHP) or transposition of the great arteries (TGA) after neonatal cardiac surgery. Methods: An exploratory online survey was performed with patients registered with the National Register for Congenital Heart Defects in Germany. For this publication, a subgroup analysis was conducted among patients diagnosed with TGA (n = 173; 36.3%) and UVHP (n = 304; 63.7%). Results: Median age of the sample at school enrollment was 6 years (range, 5-8 years). The majority were enrolled at a standard elementary school (n = 368 of 477; 77.1%), although patients with UVHP were enrolled significantly more often at a special needs school (n = 52 of 304; 17.1%, TGA patients n = 11/ of 173; 6.4%, P < .001). A total of 45.8% (n = 66 of 144) of the patients graduated with a high school diploma. A substantial number of patients had been diagnosed with behavioral or learning disorders (TGA patients n = 63 of 173 [36.4%], UVHP patients n = 148 of 304 [48.7%]) and received early supportive therapy or remedial teaching before (TGA patients n = 89 of 173 [51.4%], UVHP patients n = 209 of 304 [68.8%]) and/or during their school careers (TGA patients n = 54 of 173 [31.2%], UVHP patients n = 120 of 304 [39.5%]). Conclusions: A large proportion of patients who underwent neonatal cardiac surgery graduated with a high school diploma. These results are of great importance to congenital heart defect patients, affected families, and treating physicians. Nevertheless, study participants, especially patients with UVHP, face some academic challenges. We conclude that long-term follow-up examinations and regular developmental assessments may be beneficial.
Keywords: achievement; article; behavior disorder; career; child; controlled study; cyanotic heart disease; female; follow up; Germany; great vessels transposition; heart single ventricle; heart surgery; high school; human; learning disorder; major clinical study; male; newborn; physician; preschool child; primary school; surgery; teaching

Adolescent and parent perspectives prior to involvement in a Fontan transition program - du Plessis, K.; Culnane, E.; Peters, R.; d’Udekem, Y. (International Journal of Adolescent Medicine and Health, 2021)
Background: Successful transition to adult healthcare is particularly important for congenital heart disease (CHD) patients who have undergone palliative surgery, as they risk adverse events if not followed closely. This study examines young people at the worst end of the CHD spectrum who are born with a single ventricle (pumping heart chamber), and who undergo a series of operations that culminate in the Fontan surgical procedure. Purpose: To explore adolescents with a Fontan circulation, and their parents’, readiness for transition to adult care and pre-implementation of a transition program. Methods: Seventeen adolescents (15–18 years) and 15 of their parents completed questionnaires at the start of their first transition clinic. Results: Adolescents reported poor knowledge about their Fontan circulation, and 41% had a poor understanding of the purpose of their medications/treatments. Over half of the adolescents had poor knowledge around medical help-seeking (when, who, how). Most reported feeling comfortable with discussing their medical issues with their cardiologist, but considerably less so about sensitive adolescent issues, in particular, emotional wellbeing. Parents reported high levels of anxiety around transition to adult care services. Conclusion: Findings pre-program indicate poor adolescent health knowledge, a lack of focus in health services on emotional wellbeing and high parental anxiety. These findings highlight the need for dedicated programs that focus on early preparation, parental involvement and acknowledgment, transition as a process, strong integration and prioritisation in the health system with a youth-friendly and holistic focus, in particular, around emotional wellbeing.
Keywords: adolescent; adult; anxiety; article; cardiologist; clinical article; congenital heart disease; doctor patient relationship; experience; Fontan procedure; health service; heart single ventricle; heart surgery; help seeking behavior; human; knowledge; parent; questionnaire; transition to adult care; wellbeing; young adult

Utility of late pulmonary artery banding in single-ventricle physiology: A mid-term follow-up - Mukherji, A.; Ghosh, S.; Pathak, N.; Das, J.; Dutta, N.; Das, D.; Chattopadhyay, A. (Annals of Pediatric Cardiology, 2021)
Background: The standard first stage palliation for univentricular heart with unrestricted pulmonary blood flow (PBF) is surgical pulmonary artery (PA) banding for which the ideal age is within the first 8 weeks of life. This study aimed to look for the utility of PA band done beyond 3 months of age for patients presenting beyond the stipulated period. Materials and Methods: This is a retrospective analysis of the outcome of twenty patients with single ventricle (SV) physiology with unrestricted PBF who presented late and were selected on the basis of clinical, radiological, and echocardiographic parameters for PA banding. Results: The median age of the patients was 5.5 months (3.5-96 months), and the median body weight was 4.7 kg (3.2-22.0 kg). The patients were divided into three groups as follows: Ten patients between 3 and 6 months of age (Group A), seven patients between 6 months to 1 year of age (Group B), and three patients > 1 year of age with additional features of pulmonary venous hypertension (Group C). The mean reduction of PA pressures following PA band was 60.9%, 48.8%, and 58.3% and the mean fall in oxygen saturation was 10.4%, 8.0%, and 6.6% in the three groups, respectively. The postoperative mortality rate was 10%. The mean follow up duration was 13.5 months (7-23 months). There was a statistically significant improvement in weight for age Z scores following PA band (P = 0.0001). On follow up cardiac catheterization, the mean PA pressures were 16.6 (±3.6), 22.7 (±5.7), and 33.3 (±12.4) mmHg, respectively, in the three groups, and the mean pulmonary vascular resistance index was 1.86 (±0.5), 2.45 (±0.7), and 3.5 (±1.6) WU.m2, respectively. Subsequently, seven patients in Group A, three patients in Group B, and one patient from Group C underwent successful bidirectional Glenn (BDG) surgery. Conclusions: Late PA band in selected patients with SV physiology can have definite benefit in terms of correction of heart failure symptoms and subsequent conversion to BDG and can potentially change the natural history of disease both in terms of survival and quality of life.
Keywords: article; body weight; clinical article; controlled study; female; follow up; heart catheterization; heart failure; heart single ventricle; history; human; hypertension; infant; lung artery banding; lung artery pressure; lung blood flow; lung vascular resistance; male; oxygen saturation; pulmonary vascular disease; pulmonary vein; quality of life; retrospective study; surgical mortality; survival

Global Leadership in Paediatric and Congenital Cardiac Care: "coding our way to improved care: An interview with Rodney C. G. Franklin, MBBS, MD, FRCP, FRCPCH" - Tretter, J.T.; Jacobs, J.P. (Cardiology in the Young, 2021)
Dr Rodney Franklin is the focus of our third in a planned series of interviews in Cardiology in the Young entitled, "Global Leadership in Paediatric and Congenital Cardiac Care."Dr Franklin was born in London, England, spending the early part of his childhood in the United States of America before coming back to England. He then attended University College London Medical School and University College Hospital in London, England, graduating in 1979. Dr Franklin would then go on to complete his general and neonatal paediatrics training in 1983 at Northwick Park Hospital and University College Hospital in London, England, followed by completing his paediatric cardiology training in 1989 at Great Ormond Street Hospital for Children in London, England. During this training, he additionally would hold the position of British Heart Foundation Junior Research Fellow from 1987 to 1989. Dr Franklin would then complete his training in 1990 as a Senior Registrar and subsequent Consultant in Paediatric and Fetal Cardiology at Wilhelmina Sick Children's Hospital in Utrecht, the Netherlands. He subsequently obtained his research doctorate at University of London in 1997, consisting of a retrospective audit of 428 infants with functionally univentricular hearts. Dr Franklin has spent his entire career as a Consultant Paediatric Cardiologist at the Royal Brompton & Harefield Hospital NHS Foundation Trust, being appointed in 1991. He additionally holds honorary Consultant Paediatric Cardiology positions at Hillingdon Hospital, Northwick Park Hospital, and Lister Hospital in the United Kingdom, and Honorary Senior Lecturer at Imperial College, London. He has been the Clinical Lead of the National Congenital Heart Disease Audit (2013-2020), which promotes data collection within specialist paediatric centres. Dr Franklin has been a leading figure in the efforts towards creating international, pan European, and national coding systems within the multidisciplinary field of congenital cardiac care. These initiatives include but are not limited to the development and maintenance of The International Paediatric & Congenital Cardiac Code and the related International Classification of Diseases 11th Revision for CHD and related acquired terms and definitions. This article presents our interview with Dr Franklin, an interview that covers his experience in developing these important coding systems and consensus nomenclature to both improve communication and the outcomes of patients. We additionally discuss his experience in the development and implementation of strategies to assess the quality of paediatric and congenital cardiac care and publicly report outcomes.
Keywords: cardiologist; career; child; congenital heart disease; consensus; consultation; England; fetus; heart single ventricle; human; ICD-11; infant; interview; leadership; major clinical study; male; Netherlands; nomenclature; outcome assessment; pediatric cardiology; pediatric hospital; review; trust

Single ventricle systolic function and cardiopulmonary exercise performance in adult patients with Fontan circulation - Rybicka, J.; Dobrowolski, P.; Marczak, M.; Niewiadomska, J.; Kowalczyk, M.; Hoffman, P.; Kowalski, M. (International Journal of Cardiology, 2020)
Objective: We employed echocardiographic tissue characterization for the assessment of single ventricle systolic function and examined its relationship with cardiopulmonary exercise testing (CPET) performance in the Fontan circulation. Methods: 40 consecutive adult Fontan patients (16 female, 24 male; mean age 26.3 ± 5.9) were enrolled in our prospective cross-sectional study. All patients underwent echocardiographic assessment including tissue characterization and CPET within 3 days from each other. Results: LAPSE (lateral annular plane systolic excursion) was higher in patients with a dominant left ventricle compared to a dominant right ventricle (12.3 + −2.6 vs 9.8 + −1.1 mm, p =.008) and in patients with AP (right atrium-pulmonary artery) connection than with lateral tunnel or extracardiac conduits (13.9 ± 1.7 vs 11.3 ± 2.6 and 10.9 ± 2.2 mm, p =.014 and p =.014, respectively). Maximal oxygen pulse (O2 pulse max) was significantly higher in patients with a dominant left or common ventricle compared to patients with a dominant right ventricle (10.3 and 12.0 vs 6.6 ml/beat, p =.002 and p =.032, respectively). There was a positive correlation between O2 pulse max and LAPSE (r = 0.442, p =.009), atrioventricular valve annulus systolic velocity (S′) (r = 0.606, p <.0001), lateral wall basal segment systolic velocity (bas vel s) (r = 0.469, p =.009) and lateral wall mid segment systolic velocity (mid vel s) (r = 0.452, p =.012). In the multivariable regression model, S′ (r = 0.606, p <.0001) remained predictive of O2 pulse max. Conclusions: LAPSE and S′ are suitable parameters for the assessment of systolic function in Fontan patients. Subclinical systolic dysfunction of longitudinal fibers is associated with worse CPET performance. O2 pulse max seems to be the best parameter reflecting Fontan patients' physical performance.
Keywords: EchoPac BT09 version; mask; Oxycon Pro; real time ultrasound scanner; treadmill; ultrasound transducer; Vivid 9; ZAN Ergo 600; adolescent; adult; article; atriopulmonary connection; atrioventricular valve annulus systolic velocity; cardiopulmonary exercise test; cardiovascular parameters; child; clinical article; common ventricle; congenital heart malformation; controlled study; cross-sectional study; dominant left ventricle; dominant right ventricle; extracardiac conduit; female; Fontan procedure; heart single ventricle; heart ventricle contraction; human; human tissue; lateral annular plane systolic excursion; lateral tunnel; lateral wall basal segment systolic velocity; lateral wall mid segment systolic velocity; male; maximal oxygen pulse; physical performance; priority journal; prospective study; speckle tracking echocardiography; systolic dysfunction; task performance; tissue characterization; transthoracic echocardiography; EchoPac BT09 version; Oxycon Pro; Vivid 9; ZAN Ergo 600

Brain Development of Children With Single Ventricle Physiology or Transposition of the Great Arteries: A Longitudinal Observation Study - Hiraiwa, A.; Kawasaki, Y.; Ibuki, K.; Hirono, K.; Matsui, M.; Yoshimura, N.; Origasa, H.; Oishi, K.; Ichida, F. (Seminars in Thoracic and Cardiovascular Surgery, 2020)
To define the correlation between neuroanatomic and developmental outcomes of children with single ventricle (SV) or transposition of the great arteries (TGA), a prospective longitudinal study was performed in preschool and school-age children. Twenty-seven children with congenital heart disease (9, TGA; 18, SV) were included. Participants underwent 3-dimensional magnetic resonance imaging (MRI) and neurodevelopmental assessment at around 3 years (preschool age) and at 9 years (school age), and 48 healthy controls underwent MRI, and their data were used to derive best-fit models for normal brain volumes for comparisons with congenital heart disease patients. Total brain volume (TBV) and regional brain volumes remained significantly smaller in SV children than in TGA children at both time points, though the growth slope of TBV was not significantly different between the SV and TGA groups. Although the psychomotor developmental index at preschool was significantly lower in SV patients, the full-scale IQ at school age was not significantly lower in SV patients. There was a strong correlation between full-scale IQ and TBV (r = 0.49, P = 0.005). Despite the current best practices, persistently lower TBV was seen in SV patients until 9 years of age. For both the SV and TGA groups, TBV at 3 years was a strong predictor of TBV at 9 years. Since there was a correlation between TBV and IQ at 9 years, identification of factors that affect brain growth until 3 years will be imperative to improve patients’ cognitive function at school age.
Keywords: article; basal ganglion; body weight; brain cortex; brain development; brain size; cerebellum; child; clinical article; cognition; congenital heart disease; controlled study; corpus callosum; extracorporeal oxygenation; female; Fontan procedure; gestational age; great vessels transposition; head circumference; heart right ventricle; heart single ventricle; human; image processing; infant; longitudinal study; male; mental disease; neuroanatomy; nuclear magnetic resonance imaging; observational study; preschool child; prospective study; psychomotor development; pulmonary artery; risk factor; school child; temporal cortex; thalamus; three-dimensional imaging; white matter

Complex chromosomal rearrangements of human chromosome 21 in a patient manifesting clinical features partially overlapped with that of Down syndrome - Imaizumi, T.; Yamamoto-Shimojima, K.; Yanagishita, T.; Ondo, Y.; Nishi, E.; Okamoto, N.; Yamamoto, T. (Human Genetics, 2020)
The chromosomal region critical in Down syndrome has long been analyzed through genotype–phenotype correlation studies using data from many patients with partial trisomy 21. Owing to that, a relatively small region of human chromosome 21 (35.9 ~ 38.0 Mb) has been considered as Down syndrome critical region (DSCR). In this study, microarray-based comparative genomic hybridization analysis identified complex rearrangements of chromosome 21 in a patient manifesting clinical features partially overlapped with that of Down syndrome. Although the patient did not show up-slanting palpebral fissures and single transverse palmar creases, other symptoms were consistent with Down syndrome. Rearrangements were analyzed by whole-genome sequencing using Nanopore long-read sequencing. The analysis revealed that chromosome 21 was fragmented into seven segments and reassembled by six connected points. Among 12 breakpoints, 5 are located within the short region and overlapped with repeated segments. The rearrangement resulted in a maximum gain of five copies, but no region showed loss of genomic copy numbers. Breakpoint-junctions showed no homologous region. Based on these findings, chromoanasynthesis was considered as the mechanism. Although the distal 21q22.13 region was not included in the aberrant regions, some of the genes located on the duplicated regions, SOD1, SON, ITSN1, RCAN1, and RUNX1, were considered as possible candidate genes for clinical features of the patient. We discussed the critical region for Down syndrome, with the literature review.
Keywords: carbonyl reductase; copper zinc superoxide dismutase; DNA binding protein; DNA binding protein SON; genomic DNA; intersectin; intersectin 1; peptides and proteins; regulator of calcineurin 1; transcription factor RUNX1; unclassified drug; article; case report; child; chromosome 21; chromosome 21q; chromosome analysis; chromosome duplication; chromosome rearrangement; clinical article; clinical feature; comparative genomic hybridization; Down syndrome; droplet digital polymerase chain reaction; echocardiography; face malformation; female; finger malformation; gene location; genotype phenotype correlation; heart atrium septum defect; high arched palate; human; human cell; hypertelorism; hypoplastic left heart syndrome; leg malformation; microarray analysis; nanopore sequencing; nose malformation; partial trisomy; persistent left superior vena cava; preschool child; priority journal; pulmonary hypertension; Sanger sequencing; whole genome sequencing

Relationships between Physiologic and Neuropsychologic Functioning after Fontan - Wolfe, K.R.; Liptzin, D.R.; Brigham, D.; Kelly, S.L.; Rafferty, C.; Albertz, M.; Younoszai, A.K.; Di Maria, M.V. (Journal of Pediatrics, 2020)
Objective: To investigate potential relationships between neuropsychologic functioning and cardiac, gastroenterologic/hepatologic, and pulmonary complications in the single ventricle heart disease (SVHD) post-Fontan population. Study design: Following the initiation of a Fontan Multidisciplinary Clinic, patients with SVHD were evaluated systematically according to a clinical care pathway, and data from multiple subspecialty evaluations were collected prospectively from 2016 to 2019. Biomarkers of cardiology, pulmonary, and hepatology/gastroenterology functioning were abstracted, along with neuropsychologic testing results. Bivariate correlations and regression analyses examined cross-sectional relationships between physiologic predictors and neuropsychologic outcomes. Results: The sample included a cohort of 68 youth with SVHD age 3-19 years, after Fontan palliation. Sleep-disordered breathing was related to poorer visual-motor integration skills (r = −0.33; P < .05) and marginally related to poorer executive functioning (r = −0.33; P = .05). Lower arterial blood oxygen content was related to poorer executive functioning (r =. 45; P < .05). Greater atrioventricular valve regurgitation was related to lower parent-rated adaptive functioning (ρ = −0.34; P < .01). These results were maintained in regression analyses controlling for history of stroke and/or seizures. Conclusions: We demonstrated associations between neuropsychologic functioning and potentially modifiable aspects of physiologic functioning in a prospectively evaluated cohort of patients with SVHD with Fontan physiology. Our findings emphasize the importance of multidisciplinary screening and care after a Fontan procedure and suggest avenues for intervention that may improve patient outcomes and quality of life.
Keywords: adaptive behavior; adolescent; adult; arterial oxygen tension; article; attention; cerebrovascular accident; child; cohort analysis; comparative study; controlled study; cross-sectional study; demography; echocardiography; elastography; executive function; female; follow up; Fontan procedure; heart atrioventricular valve; heart single ventricle; human; intelligence quotient; length of stay; lung disease; major clinical study; male; neuropsychological test; outcome assessment; priority journal; prospective study; seizure; self monitoring; sleep disordered breathing; visuomotor coordination; Wechsler intelligence scale for children

Children with single ventricle congenital heart defects: An interpretative phenomenological analysis of the lived parent experience - Lumsden, M.R.; Smith, D.M.; Twigg, E.; Guerrero, R.; Wittkowski, A. (Progress in Pediatric Cardiology, 2020)
Objectives: Congenital heart defects (CHD) can be detected during routine antenatal scans or go undiagnosed until birth. Parents of children with Single Ventricle CHD (SVCHD) have a complex experience. This study aimed to explore the lived experiences of parents of children with SVCHD from diagnosis through to adolescence. Design: Interviews were conducted with 12 parents whose children had completed the Fontan procedure. Interpretative Phenomenological Analysis (IPA) identified themes across parents' accounts. Results: Data were analysed into three superordinate themes of super parents, striving for normality and accepting SVCHD and their role. Through accepting SVCHD, becoming experts, and taking responsibility for the management of their child's physical healthcare, parents developed their own sense of normality. Following distress at the point of diagnosis, parents found their own way of accepting and integrating SVCHD into family life and regained a sense of control and normality within the family. Conclusions: Transition points such as starting nursery, final surgery, puberty, and reaching adulthood are key time points when parents may struggle with their changing roles and the gradual shift of responsibility and independence onto their children. There are implications for supporting parents to educate their children in terms of the management and long-term prognosis of their condition, especially when the child with SVCHD enters puberty or moves into adult services where they gain agency of their condition and its management. The role of healthcare professionals promoting emotional wellbeing and providing support to families during significant periods is discussed.
Keywords: adolescent; adult; article; child; child care; clinical article; congenital heart disease; data analysis; female; Fontan procedure; heart single ventricle; human; interpretative phenomenological analysis; male; parent; peer group; personal experience; phenomenology; priority journal; responsibility; school child; sibling; time to treatment; young adult

Health-related quality of life correlates with time in therapeutic range in children on anticoagulants with International Normalised Ratio self-monitoring - Abassi, H.; Bajolle, F.; Werner, O.; Auer, A.; Marquina, A.; Mura, T.; Lavastre, K.; Guillaumont, S.; Manna, F.; Auquier, P.; Bonnet, D.; Amedro, P. (Archives of Cardiovascular Diseases, 2020)
Background: Managing oral anticoagulant therapy with vitamin K antagonists remains challenging in paediatric medicine. Aims: This study aimed to assess the correlation between time in therapeutic range and quality of life in children participating in a non-selective International Normalised Ratio self-monitoring and vitamin K antagonist education programme. Methods: Children aged from 2 to 18 years and receiving vitamin K antagonist therapy were eligible for this prospective multicentre study. Clinical and demographic data were collected. Health-related quality of life was assessed using the PedsQL™ 4.0 questionnaire. Correlations between quality of life scores and time in therapeutic range were measured. Results: A total of 121 children were included in the study (mean age 9.6 ± 4.9 years). Cardiac conditions were the predominant indication for vitamin K antagonists. The mean time in therapeutic range was 0.78 ± 0.15 overall, and 0.76 ± 0.24 over the 3-month period before quality of life assessment. The mean total quality of life score was 76.2 ± 18 in self reports, 71.4 ± 22 in mother reports and 73.5 ± 19 in father reports. The time in therapeutic range correlated with the total quality of life scores in self reports (r = 0.22; P = 0.04), mother reports (r = 0.23; P = 0.02) and father reports (r = 0.28; P = 0.02). The time in therapeutic range predominantly correlated with school functioning in self reports (r = 0.38; P = 0.002) and mother reports (r = 0.40; P < 0.001), and with physical functioning in father reports (r = 0.28; P = 0.03). Conclusions: Time in therapeutic range correlated with quality of life in children participating in a non-selective International Normalised Ratio self-monitoring and vitamin K antagonist education programme. Regular assessment of quality of life in patient education programmes contributes towards understanding the concerns and needs of patients.
Keywords: CoaguChek XS; CoaguChek XS Connect software; coagulometer; antivitamin K; adolescent; adult; anticoagulant therapy; article; child; controlled study; correlation analysis; cross-sectional study; diagnosis; education program; emotionality; female; Fontan procedure; human; international normalized ratio; Likert scale; major clinical study; male; mother; multicenter study; patient education; Pediatric Quality of Life Inventory; prospective study; quality of life; quality of life assessment; self monitoring; self report; social interaction; social psychology; CoaguChek XS; CoaguChek XS Connect software

Socioeconomic status and long-term outcomes in single ventricle heart disease - Bucholz, E.M.; Sleeper, L.A.; Goldberg, C.S.; Pasquali, S.K.; Anderson, B.R.; William Gaynor, J.; Cnota, J.F.; Newburger, J.W. (Pediatrics, 2020)
BACKGROUND: Low socioeconomic status (SES) has emerged as an important risk factor for higher short-term mortality and neurodevelopmental outcomes in children with hypoplastic left heart syndrome and related anomalies; yet little is known about how SES affects these outcomes over the long-term. METHODS: We linked data from the Single Ventricle Reconstruction trial to US Census Bureau data to analyze the relationship of neighborhood SES tertiles with mortality and transplantation, neurodevelopment, quality of life, and functional status at 5 and 6 years post–Norwood procedure (N = 525). Cox proportional hazards regression and linear regression were used to assess the association of SES with mortality and neurodevelopmental outcomes, respectively. RESULTS: Patients in the lowest SES tertile were more likely to be racial minorities, older at stage 2 and Fontan procedures, and to have more complications and fewer cardiac catheterizations over follow-up (all P, .05) compared with patients in higher SES tertiles. Unadjusted mortality was highest for patients in the lowest SES tertile and lowest in the highest tertile (41% vs 29%, respectively; log-rank P = .027). Adjustment for patient birth and Norwood factors attenuated these differences slightly (P = .055). Patients in the lowest SES tertile reported lower functional status and lower fine motor, problem-solving, adaptive behavior, and communication skills at 6 years (all P, .05). These differences persisted after adjustment for baseline and post-Norwood factors. Quality of life did not differ by SES. CONCLUSIONS: Among patients with hypoplastic left heart syndrome, those with low SES have worse neurodevelopmental and functional status outcomes at 6 years. These differences were not explained by other patient or clinical characteristics.
Keywords: adaptive behavior; article; communication skill; female; follow up; Fontan procedure; functional status; heart catheterization; heart single ventricle; heart transplantation; human; major clinical study; male; mortality rate; motor performance; nervous system development; newborn; Norwood procedure; priority journal; problem solving; quality of life; race; risk factor; socioeconomics

Traversing the liminal: What can Fontan adults' transition experiences and perspectives teach us about optimizing healthcare? - Du Plessis, K.; Peters, R.; Culnane, E.; D'Udekem, Y. (International Journal of Adolescent Medicine and Health, 2020)
Successfully transitioning to adult care is important for congenital heart disease (CHD) patients, particularly those at the worst end of the spectrum with a Fontan circulation, as their ongoing health engagement affects their health outcomes. Yet, there is a lack of literature exploring patient perspectives about their transition experiences, and what helps or hinders successful transition to adult care. Young adults with a Fontan circulation (n = 18) from the Australian and New Zealand Fontan Registry participated in in-depth phone interviews. Thematic analyses were used to analyze the qualitative interview data. We identified six key themes which stood out from patient experiences, including differences between pediatric and adult congenital cardiac care, the need for preparation through formal transition programs, and the important role of support systems. To become active managers of their healthcare and remain engaged with the healthcare system, young people would benefit from coordinated efforts between pediatric and adult care to formally prepare them for transition to adult care. This should include involvement from their support network and ongoing education about their health condition. The study highlights the importance of studying patient perspectives through qualitative research to better inform health service provision in the CHD space.
Keywords: adult; article; Australia; clinical article; congenital heart disease; female; follow up; Fontan procedure; health behavior; health care; health care system; human; interview; male; New Zealand; patient education; qualitative research; thematic analysis; transition to adult care; young adult

Data Quality Assessment on Congenital Anomalies in Ontario, Canada - Miao, Q.; Moore, A.M.; Dougan, S.D. (Frontiers in Pediatrics, 2020)
Background: Congenital anomalies (CAs) are a major cause of infant morbidity and mortality in Canada. Reliably identifying CAs is essential for CA surveillance and research. The main objective of this study was to assess the agreement of eight sentinel anomalies including: neural tube defects (NTD), orofacial clefts, limb deficiency defects (LDD), Down syndrome (DS), tetralogy of Fallot (TOF), gastroschisis (GS), hypoplastic left heart syndrome (HLHS) and transposition of great vessels (TGA) captured in the BORN Information System (BIS) database and the Canadian Institute for Health Information (CIHI) Discharge Abstract Database (DAD). Methods: Live birth and stillbirth records between the BIS and CIHI-DAD in the fiscal years of 2012–2013 to 2015–2016 were linked using 10 digit infant Ontario Health Insurance Plan (OHIP) numbers. Percent agreement and Kappa statistics were performed to assess the reliability (agreement) of CAs identified in the linked BIS and CIHI-DAD birth records. Then, further investigations were conducted on those CA cases identified in the CIHI-DAD only. Results: Kappa coefficients of the eight selected CAs between BIS (“Confirmed” or “Suspected” cases) and CIHI-DAD were 0.96 (95% CI: 0.93–0.98) for GS; 0.81 (95% CI: 0.78–0.83) for Orofacial clefts; 0.75 (95% CI: 0.72–0.77) for DS; 0.71 (95% CI: 0.65–0.77) for TOF; 0.62 (95% CI: 0.55–0.68) for TGA; 0.59 (95% CI: 0.49–0.68) for HLHS, 0.53 (95% CI: 0.46–0.60) for NTD-all; and 0.30 (95% CI: 0.23–0.37) for LDD. Conclusions: The degree of agreement varied among sentinel CAs identified between the BIS and CIHI. The potential reasons for discrepancies include incompleteness of capturing CAs using existing picklist values, especially for certain sub-types, incomplete neonatal special care data in the BIS, and differences between clinical diagnosis in the BIS and ICD-10-CA classification in the DAD. A future data abstraction study will be conducted to investigate the potential reasons for discrepancies of CA capture between two databases. This project helps quantify the quality of CA data collection in the BIS, enhances understanding of CA prevalence in Ontario and provides direction for future data quality improvement activities.
Keywords: article; cleft face; clinical assessment; congenital malformation; data quality assessment; Down syndrome; Fallot tetralogy; fetus; gastroschisis; gestational age; great vessels transposition; human; hypoplastic left heart syndrome; ICD-10; infant; kappa statistics; limb defect; live birth; neural tube defect; Ontario; prevalence; stillbirth

Case Report: Characterization of a Novel NONO Intronic Mutation in a Fetus With X-Linked Syndromic Mental Retardation-34 - Sun, H.; Han, L.; Zhang, X.; Hao, X.; Zhou, X.; Pan, R.; Zhang, H.; He, Y. (Frontiers in Genetics, 2020)
Background: The NONO gene is located on chromosome Xq13.1 and encodes a nuclear protein involved in RNA synthesis, transcriptional regulation, and DNA repair. Hemizygous variants in NONO have been reported to cause mental retardation, X-linked, syndromic 34 (MRXS34) in males. Due to the scarcity of clinical reports, the clinical characteristics and mutation spectrum of NONO-related disorder have not been entirely determined. Methods: We reported a fetus with hypoplastic left heart syndrome, performed a comprehensive genotyping examination, including copy-number variation sequencing and whole-exome sequencing, and screened for the genetic abnormality. We also conducted an in vitro mini-gene splicing assay to demonstrate the predicted deleterious effects of an intronic variant of NONO. Results: Exome sequencing identified a novel intronic variant (c.154 + 9A > G) in intron 4 of the NONO gene (NM_001145408.1). It was predicted to insert 4 bp of intron 4 into the mature mRNA. Minigene assay revealed that the c.154 + 9A > G variant caused the activation of the intronic cryptic splice site and 4 bp insertion (c.154_155ins GTGT) in mature mRNA. Literature review shows that cardiac phenotype, including left ventricular non-compaction cardiomyopathy and congenital heart disease, are consistent features of MRXS34. Conclusion: This study enlarges the mutation spectrum of NONO, further expands hypoplastic left heart syndrome to the phenotype of MRXS34 and points out the importance of intronic sequence analysis and the need for integrative functional studies in the interpretation of sequence variants.
Keywords: fetal ultrasound monitor; messenger RNA; adult; agar gel electrophoresis; aorta hypoplasia; article; autopsy; cardiomyopathy; case report; chromosome aberration; chromosome Xq; chromosome Xq 13.1; clinical article; color Doppler echocardiography; computer model; congenital heart disease; copy number variation; DNA repair; DNA vector; dysplasia; eukaryotic cell; female; fetus; gene; gene frequency; gene mutation; gene sequence; genetic disorder; genetic transfection; genetic variability; genotype; hemizygous variant; human; human tissue; hypoplasia; hypoplastic left heart syndrome; hypoplastic left ventricle dysplasia; in silico splicing analysis; intron; intronic variant; M mode echocardiography; mental deficiency; mini gene splicing assay; mitral valve dysplasia; NONO p54nrb; phenotype; pulsed Doppler echocardiography; real time polymerase chain reaction; RNA splicing; RNA synthesis; sequence analysis; splicing vector pEGFP C1; transcription regulation; two dimensional echocardiography; ultraviolet spectrophotometry; ventricular noncompaction; whole exome sequencing; X linked syndromic 34; young adult

Trisomy 21 Patients Undergoing Cavopulmonary Connections Need Improved Pre- and Postoperative Care - Allen, P.; Anderson, B.R.; Bacha, E.; LaPar, D.J. (The Annals of thoracic surgery, 2020)
BACKGROUND: Trisomy 21 (T21) patients often have elevated pulmonary vascular resistance, which may result in suboptimal cavopulmonary connection (CPC) following Glenn or Fontan operations. The purpose of this study was to assess in a nationwide, multi-institution cohort of CPC patients the impact of T21 on patient morbidity, mortality, and resource utilization. METHODS: A total of 23,271 CPC pediatric patients (2004 - 2019) at 50 U.S. hospitals were evaluated using the Pediatric Health Information System (PHIS) database. Univariable and multivariable regression analyses were used to assess risk-adjusted associations between Down syndrome and other risk factors and postoperative measures of morbidity, mortality, lengths of stay (LOS) and cost of hospitalization. RESULTS: The overall prevalence of T21 among Glenn and Fontan patients was 1.5% (199/13,268) and 0.8% (78/1,003), respectively. Among both CPC cohorts, T21 status significantly increased unadjusted mortality, hospital lengths of stay and total costs of hospitalization compared to non-T21 CPC patients (all P < 0.001). T21 patients also incurred a higher incidence of prolonged mechanical ventilation compared to non-T21 patient in both Glenn and Fontan patients (P < 0.001). Multivariable regression analysis further estimated that T21 patients are associated with a 5.5-fold increase in mortality (P < 0.001) compared to non-T21 patients. Lastly, T21 patients had increased long-term mortality compared to their peers. CONCLUSIONS: Trisomy 21 significantly increases risk-adjusted morbidity, inpatient mortality, long-term mortality and resource utilization following cavopulmonary connections. Further investigation is needed to clarify modifiable patient-level and center-specific risk factors to improve outcomes for T21 patients.
Keywords: article; artificial ventilation; cavopulmonary connection; child; cohort analysis; controlled study; Down syndrome; female; hospital mortality; hospitalization; human; length of stay; major clinical study; male; medical information system; morbidity; pediatric patient; postoperative care; prevalence; risk assessment; risk factor

Intrauterine Growth Restriction and Hypertrophic Cardiomyopathy as Prenatal Ultrasound Findings in a Case of Leprechaunism - Perge, K.; Massoud, M.; Gauthier-Moulinier, H.; Lascols, O.; Pangaud, N.; Villanueva, C.; Pons, L. (Molecular Syndromology, 2020)
Donohue syndrome (leprechaunism; OMIM ∗246200) is a rare and often lethal autosomal recessive disease caused by mutations in the INSR gene. We report the case of a 29-year-old pregnant woman, primigravida, who was referred at 33 weeks of gestation for severe intrauterine growth restriction (IUGR). Ultrasound examination found severe IUGR associated with an obstructive hypertrophic cardiomyopathy (HCM), confirmed postnatally. The newborn's blood glucose level fluctuated from fasting hypoglycemia to postprandial hyperglycemia. The infant was found to be homozygous for a novel missense pathogenic variant, c.632C>T (p.T211l), in exon 2 of the INSR gene, predicted to result in an abnormal insulin receptor. To our knowledge, this is the first report of leprechaunism being revealed by IUGR and HCM during the prenatal period. Clinicians should keep in mind that the association of these prenatal signs could indicate leprechaunism and specific early neonatal management could be proposed, in particular with recombinant human insulin-like growth factor-I.
Keywords: blood clotting factor 7; C peptide; chorionic gonadotropin; insulin; pregnancy associated plasma protein A; propranolol; recombinant somatomedin C; adult; anemia; aortic occlusion; article; carbohydrate intake; case report; clinical article; clinical assessment; clinical feature; continuous infusion; crown rump length; Doppler flowmetry; drug megadose; ear malformation; echocardiography; exophthalmos; fasting; female; fetus echography; fetus weight; genetic association; heart right ventricle outflow tract obstruction; human; hyperglycemia; hypertrichosis; hypertrophic cardiomyopathy; hypoalbuminemia; hypoglycemia; hypoplastic left heart syndrome; intrauterine growth retardation; leprechaunism; male; missense mutation; necrotizing enterocolitis; newborn; noninvasive ventilation; nuchal translucency measurement; pediatric patient; pericardial effusion; pregnancy; pregnant woman; prenatal diagnosis; prenatal period; primigravida; priority journal; prothrombin time; respiratory distress; Sanger sequencing; thrombocytopenia; ulcerative colitis

Case Report: Disseminated Systemic Embolism of Lipiodol After Lymphography for Plastic Bronchitis After Fontan Repair - Hubrechts, J.; Wåhlander, H.; Kjellberg-Olofsson, C.; Maleux, G.; Gewillig, M. (Frontiers in Pediatrics, 2020)
Lipiodol-based lymphangiography is not only a diagnostic tool for visualization of lymphatic disorders such as plastic bronchitis (PB), but also aims a therapeutic effect by embolizing lymph leakages. We performed such percutaneous lymphatic embolization for PB in a Fontan patient with proven absence of right-to-left shunt, and demonstrated important lymphatic abnormalities in the mediastinum. Shortly after the procedure, the patient developed severe convulsive seizures, revealing multiple cerebral embolisms of Lipiodol. Radiological images were impressive, yet the clinical neurological outcome was favorable. Lipiodol-based lymphography in Fontan patients with plastic bronchitis should be avoided as this subgroup is more likely to have developed lympho-pulmonary venous connections which allow systemic emboli.
Keywords: spinal needle; ultrasound transducer; clonidine; diazepam; hypertensive factor; inotropic agent; iodinated poppyseed oil; levetiracetam; midazolam; prednisone; acute kidney failure; aortic coarctation; article; artificial embolization; brain embolism; bronchitis; case report; cavopulmonary connection; child; chylothorax; clinical article; clinical outcome; cone beam computed tomography; dysthymia; fluoroscopy; Fontan procedure; heart atrium septum defect; heart right left shunt; heart ventricle septum defect; human; liver dysfunction; lymphangiography; male; mediastinum; multiple organ failure; neuroimaging; oliguria; palliative therapy; plastic bronchitis; pulmonary artery catheterization; school child; seizure; spasticity; susceptibility weighted imaging; systemic disease; unconsciousness; lipiodol ultrafluid

Development of a validated risk score for interstage death or transplant after stage I palliation for single-ventricle heart disease - Ahmed, H.; Anderson, J.B.; Bates, K.E.; Fleishman, C.E.; Natarajan, S.; Ghanayem, N.S.; Sleeper, L.A.; Lannon, C.M.; Brown, D.W. (Journal of Thoracic and Cardiovascular Surgery, 2020)
Objective: To develop a risk score to predict mortality or transplant in the interstage period. Background: The “interstage” period between the stage 1 and stage 2 palliation is a time of high morbidity and mortality for infants with single-ventricle congenital heart disease. Methods: This was an analysis of patients with single-ventricle congenital heart disease requiring arch reconstruction who were enrolled in the National Pediatric Cardiology Quality Improvement Collaborative registry from 2008 to 2015. The primary composite endpoint was interstage mortality or transplant. Multivariable logistic regression and classification and regression tree analysis were performed on two-thirds of the patients (“learning cohort”) to build a risk score for the composite endpoint, that was validated in the remaining patients (“validation cohort”). Results: In the 2128 patients analyzed in the registry, the overall event rate was 9% (153 [7%] deaths, 42 [2%] transplants). In the learning cohort, factors independently associated with the composite endpoint were (1) type of Norwood; (2) postoperative ECMO; (3) discharge with Opiates; (4) No Digoxin at discharge; (5) postoperative Arch obstruction, (6) moderate-to-severe Tricuspid regurgitation without an oxygen requirement, and (7) Extra Oxygen required at discharge in patients with moderate-to-severe tricuspid regurgitation. This model was used to create a weighted risk score (“NEONATE” score; 0-76 points), with >75% accuracy in the learning and validation cohorts. In the validation cohort, the event rate in patients with a score >17 was nearly three times those with a score ≤17. Conclusions: We introduce a risk score that can be used post-stage 1 palliation to predict freedom from interstage mortality or transplant.
Keywords: acetylsalicylic acid; antiarrhythmic agent; benzodiazepine derivative; beta adrenergic receptor blocking agent; clonidine; clopidogrel; digoxin; dipeptidyl carboxypeptidase inhibitor; diuretic agent; enoxaparin; opiate; spironolactone; aortic arch surgery; article; birth weight; cohort analysis; controlled study; disease registry; disease severity; echocardiography; extracorporeal oxygenation; female; follow up; gestational age; heart right ventricle double outlet; heart single ventricle; human; hypoplastic left heart syndrome; major clinical study; male; morbidity; mortality rate; oxygen consumption; palliative therapy; personal experience; priority journal; prospective study; quality of life; right ventricle to pulmonary artery conduit; scoring system; systolic dysfunction; tricuspid valve regurgitation

Caudate nuclei volume alterations and cognition and mood dysfunctions in adolescents with single ventricle heart disease - Noorani, S.; Roy, B.; Sahib, A.K.; Cabrera-Mino, C.; Halnon, N.J.; Woo, M.A.; Lewis, A.B.; Pike, N.A.; Kumar, R. (Journal of Neuroscience Research, 2020)
Adolescents with single ventricle heart disease (SVHD) exhibit mood and cognitive deficits, which may result from injury to the basal ganglia structures, including the caudate nuclei. However, the integrity of the caudate in SVHD adolescents is unclear. Our aim was to examine the global and regional caudate volumes, and evaluate the relationships between caudate volumes and cognitive and mood scores in SVHD and healthy adolescents. We acquired two high-resolution T1-weighted images from 23 SVHD and 37 controls using a 3.0-Tesla MRI scanner, as well as assessed mood (Patient Health Questionnaire-9 [PHQ-9]; Beck Anxiety Inventory [BAI]) and cognition (Montreal Cognitive Assessment [MoCA]; Wide Range Assessment of Memory and Learning–2; General Memory Index [GMI]) functions. Both left and right caudate nuclei were outlined, which were then used to calculate and compare volumes between groups using ANCOVA (covariates: age, gender, and head-size), as well as perform 3D surface morphometry. Partial correlations (covariates: age, gender, and head-size) were used to examine associations between caudate volumes, cognition, and mood scores in SVHD and controls. SVHD subjects showed significantly higher PHQ-9 and BAI scores, indicating more depressive and anxiety symptoms, as well as reduced GMI scores, suggesting impaired cognition, compared to controls. SVHD patients showed significantly reduced caudate volumes (left, 3,198.8 ± 490.1 vs. 3,605.0 ± 480.4 mm3, p < 0.004; right, 3,162.1 ± 475.4 vs. 3,504.8 ± 465.9 mm3, p < 0.011) over controls, and changes were localized in the rostral, mid-dorsolateral, and caudal areas. Significant negative correlations emerged between caudate volumes with PHQ-9 and BAI scores and positive correlations with GMI and MoCA scores in SVHD and controls. SVHD adolescents show significantly reduced caudate volumes, especially in sites that have projections to regulate mood and cognition, which may result from developmental and/or hypoxia-/ischemia-induced processes.
Keywords: imaging software; nuclear magnetic resonance scanner; adolescent; anxiety disorder; article; attention; Beck Anxiety Inventory; brain region; brain size; caudate nucleus; cerebrospinal fluid; clinical article; cognition; comparative study; conceptual thinking; controlled study; depression; dorsolateral striatum; executive function; female; General Memory Index; gray matter; heart single ventricle; human; language; left caudate nucleus; male; memory; memory assessment; Montreal cognitive assessment; mood disorder; morphometry; neuroimaging; nuclear magnetic resonance imaging; orientation; Patient Health Questionnaire 9; priority journal; right caudate nucleus; verbal memory; visual memory; white matter; Wide Range Assessment of Memory and Learning 2; working memory; Magnetom Prisma; statistical parametric mapping

The Spectrum of Cardiac Anomalies Associated with Heterotaxy: A Single-Center Study of a Large Series Based on Computed Tomography - Kiran, V.S.; Choudhary, S.; Shaik, A.; Gadabanahalli, K.; Raj, V.; Bhat, V. (Pediatric Cardiology, 2020)
The aim of the study was to identify and correlate the anatomical variants of cardiac structures among patients with heterotaxy. In this retrospective cross-sectional analysis of 13 years duration, 302 patients of congenital heart diseases associated with heterotaxy were studied. All these patients had undergone a meticulous clinical evaluation, echocardiography, and cardiac computed tomography. The mean age of the cohort was 38.4 months, with 180 males and 122 females. The cohort had 184 patients of right isomerism and 118 of left isomerism. More than half of the cohort had abnormal pulmonary veins. Over 75% of the cohort had low pulmonary blood flow. Abnormal relationship of great arteries was seen in nearly 69% of the cohort. Atrio-venticular canal defect was the commonest anatomical variant. Overall, 43% of the cohort had single ventricle physiology, predominantly associated with right isomerism. Heterotaxy forms a difficult anatomical subset to comprehend due to the plethora of possible abnormalities. However, unless the cardiac and visceral anatomy is delineated well, the surgical plan becomes suboptimal and often elusive, leaving tough choices for cardiac surgeon. It is essential to obtain all the possible anatomical information using additional imaging modalities to devise a basis for a comprehensive plan for medical and surgical management. A better understanding of the genetic and molecular factors in the etiology, coupled with the application of state-of-the-art imaging techniques, is likely to add to our knowledge of heterotaxy to bring about improved surgical outcomes and a better quality of life for patients suffering from this complex entity.
Keywords: anatomical variation; article; atrioventricular canal; child; clinical evaluation; cohort analysis; computer assisted tomography; congenital heart malformation; controlled study; cross-sectional study; disease association; disease duration; echocardiography; female; heterotaxy syndrome; human; image analysis; infant; major clinical study; male; preschool child; quality of life; retrospective study; treatment outcome

Parental mobile health adherence to symptom home monitoring for infants with congenital heart disease during the single ventricle interstage period: A concept analysis - Erickson, L.A.; Emerson, A.; Russell, C.L. (Journal for Specialists in Pediatric Nursing, 2020)
Purpose: Single ventricle heart disease is fraught with risk for infant mortality and morbidity. During the interstage period, or the time between palliative cardiac surgeries, mobile health (mHealth) technology improves the ability of registered nurse coordinators to monitor infant symptoms through parental monitoring and reporting. The concept of parental mHealth adherence to symptom home monitoring of infants with single ventricle congenital heart disease has not been defined, despite increasing use of mHealth technology. Methods: Rodger's concept analysis method was used to derive a unified definition of parental mHealth adherence to symptom home monitoring of infants with congenital heart disease during the single ventricle interstage period. A literature review included a search of databases for studies that addressed interstage home mHealth monitoring. Thematic analysis was applied to selected articles to derive a unified definition based on attributes, antecedents, consequences, related terms, and an illustrative case example. Sixteen publications were selected. Attributes, antecedents, and consequences of the concept were derived from the literature leading to a definition of parental mHealth adherence for infants with congenital heart disease during the single ventricle interstage period. The definition is the degree of adherence to which parents' transfer mHealth data for their infant meet healthcare providers' recommendations for symptom home monitoring. Consequences were improved infant symptom home monitoring through parental mHealth adherence measured by initiation, implementation, and discontinuation. Conclusion: The unified definition of the concept will provide a firmer ground for research in mHealth and interstage pediatric care and a guide for clinicians in developing new mHealth interventions for symptom home monitoring. Practice Implications: This concept analysis hypothesizes that infants with a single ventricle during the interstage period, whose parents are mHealth symptom home monitoring adherent, will have timelier symptom identification with resultant superior outcomes compared with infants with a single ventricle during the interstage period whose parents are not mHealth adherent.
Keywords: article; child growth; congenital heart disease; family functioning; field hospital; health care delivery; health care personnel; health care system; hospital readmission; hospitalization; human; infant; infant mortality; medication compliance; mobile application; morbidity; mortality; oxygen saturation; prenatal diagnosis; priority journal; randomized controlled trial (topic); risk factor; social determinants of health; telemedicine; thematic analysis; three dimensional echocardiography

The impact of prenatal counselling on mothers of surviving children with hypoplastic left heart syndrome: A qualitative interview study - Bertaud, S.; Lloyd, D.F.A.; Sharland, G.; Razavi, R.; Bluebond-Langner, M. (Health expectations : an international journal of public participation in health care and health policy, 2020)
OBJECTIVE: To explore the role of antenatal counselling in how parents make treatment decisions following an antenatal diagnosis of Hypoplastic Left Heart Syndrome (HLHS). BACKGROUND: Antenatal counselling is a critical part of patient management following a diagnosis of fetal congenital heart disease; however, there is a very limited evidence base examining how parents actually experience antenatal counselling and make decisions in this context. METHODS: Semi-structured interviews were conducted with women who had received an antenatal diagnosis of HLHS. Interviews were digitally recorded, anonymised and transcribed verbatim. A thematic content analysis was performed using a constant comparative approach. RESULTS: Eight mothers of surviving children with HLHS were interviewed. Eight key themes emerged including new perspectives on how women receive antenatal counselling and how it affects their decision making. Three themes in particular are new to the literature: (a) Mothers of children with HLHS reported feelings of intense guilt that arose in the antenatal period around potentially causing the condition in their child. (b) For this group of women, recollections of perceived pessimism during antenatal counselling had a lasting impact. (c) Despite support from partners or extended family, women nevertheless experienced a strong sense that antenatal decision making was largely a 'maternal' responsibility. CONCLUSIONS: When recounting their experiences of antenatal counselling, mothers of surviving children with HLHS offer new perspectives that can guide fetal cardiologists in how best to support their individual patients. Further research is needed to comprehensively understand the experience of prospective parents counselled for severe forms of fetal congenital heart disease.
Keywords: article; cardiologist; child; clinical article; content analysis; controlled study; counseling; decision making; extended family; female; fetus; genetic transcription; guilt; human; hypoplastic left heart syndrome; interview; mother; pessimism; prenatal diagnosis; prenatal period; responsibility

Periconceptional use of cod liver oil, a vitamin D source, could decrease the risk of CHD in offspring - Zhao, A.; Zhao, K.; Xia, Y.; Yin, Y.; Zhu, J.; Hong, H.; Li, S. (Cardiology in the Young, 2020)
Objective: To explore if there is association between vitamin D supplementation through cod liver oil ingestion around the periconceptional period and the risk of developing severe CHD in offspring. Furthermore, we would examine the interaction between vitamin D and folic acid supplementation in the association. Methods: A case-control study was conducted in Shanghai Children's Medical Center, in which, a total of 262 severe CHD cases versus 262 controls were recruited through June 2016 to December 2017. All children were younger than 2 years. To reduce potential selection bias and to minimise confounding effects, propensity score matching was applied. Results: After propensity score matching, vitamin D supplementation seemed to be associated with decreased odds ratio of severe CHD (odds ratio = 0.666; 95% confidence intervals: 0.449-0.990) in the multivariable conditional logistic analysis. Furthermore, we found an additive interaction between vitamin D and folic acid supplementation (relative excess risk due to interaction = 0.810, 95% confidence intervals: 0.386-1.235) in the association. Conclusion: The results suggested that maternal vitamin D supplementation could decrease the risk of offspring severe CHD; moreover, it could strengthen the protective effect of folic acid. The significance of this study lies in providing epidemiological evidence that vitamin D supplementation around the periconceptional period could be a potential nutritional intervention strategy to meet the challenge of increasing CHD.
Keywords: cod liver oil; folic acid; vitamin D; aortic arch interruption; article; atrioventricular septal defect; case control study; child; China; congenital heart disease; congenital mitral stenosis; controlled study; disease severity; Fallot tetralogy; female; great vessels transposition; heart right ventricle double outlet; heart single ventricle; hospital based case control study; human; hypoplastic left heart syndrome; infant; lung vein drainage anomaly; major clinical study; male; propensity score; pulmonary valve atresia; risk reduction; single atrium; tricuspid valve atresia; vitamin supplementation

Socioeconomic Status and Long-term Outcomes in Single Ventricle Heart Disease - Bucholz, E.M.; Sleeper, L.A.; Goldberg, C.S.; Pasquali, S.K.; Anderson, B.R.; Gaynor, J.W.; Cnota, J.F.; Newburger, J.W. (Pediatrics, 2020)
BACKGROUND: Low socioeconomic status (SES) has emerged as an important risk factor for higher short-term mortality and neurodevelopmental outcomes in children with hypoplastic left heart syndrome and related anomalies; yet little is known about how SES affects these outcomes over the long-term. METHODS: We linked data from the Single Ventricle Reconstruction trial to US Census Bureau data to analyze the relationship of neighborhood SES tertiles with mortality and transplantation, neurodevelopment, quality of life, and functional status at 5 and 6 years post-Norwood procedure (N = 525). Cox proportional hazards regression and linear regression were used to assess the association of SES with mortality and neurodevelopmental outcomes, respectively. RESULTS: Patients in the lowest SES tertile were more likely to be racial minorities, older at stage 2 and Fontan procedures, and to have more complications and fewer cardiac catheterizations over follow-up (all P < .05) compared with patients in higher SES tertiles. Unadjusted mortality was highest for patients in the lowest SES tertile and lowest in the highest tertile (41% vs 29%, respectively; log-rank P = .027). Adjustment for patient birth and Norwood factors attenuated these differences slightly (P = .055). Patients in the lowest SES tertile reported lower functional status and lower fine motor, problem-solving, adaptive behavior, and communication skills at 6 years (all P < .05). These differences persisted after adjustment for baseline and post-Norwood factors. Quality of life did not differ by SES. CONCLUSIONS: Among patients with hypoplastic left heart syndrome, those with low SES have worse neurodevelopmental and functional status outcomes at 6 years. These differences were not explained by other patient or clinical characteristics.
Keywords: child; child development; clinical trial; complication; controlled study; demography; developmental disorder; educational status; ethnology; female; Fontan procedure; heart catheterization; heart single ventricle; heart transplantation; human; hypoplastic left heart syndrome; income; male; mortality; multicenter study; newborn; occupation; postoperative complication; preschool child; procedures; proportional hazards model; quality of life; randomized controlled trial; social class; treatment outcome

Acellular dermal matrix reconstruction of a nail bed avulsion in a 13-year-old child - Kiely, A.L.; Cooper, L.R.L.; Greig, A. (BMJ Case Reports, 2020)
Nail bed avulsion injuries often require reconstruction, particularly in cases where the avulsed fragment is lost. We describe a simple way to reconstruct a large nail bed defect, with no donor site. A 13-year-old boy with a hypoplastic left heart and autism accidentally sustained a left little distal phalanx injury with an avulsion of 60% of the nail bed, exposing the distal phalanx. This boy had a history of poor compliance, qualifying the need to find a technique that would minimise operative time and dressing changes. As such, it was elected to use an acellular dermal matrix (ADM) (Matriderm) as a one-step reconstruction. Signs of vascularisation of the ADM were noted at 2 weeks, and 3-month follow-up demonstrated integration, with normal nail growth. We found that Matriderm was able to support the regeneration of a full thickness wound in a simple one-step procedure.
Keywords: acellular dermal matrix; Matriderm; polyglactin suture; surgical implant template; wound dressing; antibiotic agent; acellular dermal matrix reconstruction; adolescent; article; autism; case report; clinical article; finger tip injury; follow up; human; hypoplastic left heart syndrome; male; nail bed; nail infection; outcome assessment; priority journal; skin surgery; tetanus; Matriderm; Vicryl Rapide

A low incidence of preoperative neurosonographic abnormalities in neonates with heart defects - Jansen, F.A.R.; Haak, M.C.; van Wesemael, M.S.; ten Harkel, A.D.J.D.-J.; van Lith, J.M.M.; Blom, N.A.; Steggerda, S.J. (Early Human Development, 2020)
Background and aim: To investigate whether neonates with prenatally detected congenital heart defects (CHD) demonstrate cerebral abnormalities on early preoperative cranial ultrasound (CUS), compared to healthy neonates, and to measure brain structures to assess brain growth and development in both groups. Study design, subjects and outcome measures: Prospective cohort study with controls. Between September 2013 and May 2016 consecutive cases of prenatally detected severe isolated CHD were included. Neonatal CUS was performed shortly after birth, before surgery and in a healthy control group. Blinded images were reviewed for brain abnormalities and various measurements of intracranial structures were compared. Results: CUS was performed in 59 healthy controls and 50 CHD cases. Physiological CUS variants were present in 54% of controls and in 52% of CHD cases. Abnormalities requiring additional monitoring (both significant and minor) were identified in four controls (7%) and five CHD neonates (10%). Significant abnormalities were only identified in four CHD neonates (8%) and never in controls. A separate analysis of an additional 8 CHD neonates after endovascular intervention demonstrated arterial stroke in two cases that underwent balloon atrioseptostomy (BAS). Cerebral measurements were smaller in CHD neonates, except for the cerebrospinal fluid measurements, which were similar to the controls. Conclusions: The prevalence of significant preoperative CUS abnormalities in CHD cases was lower than previously reported, which may be partially caused by a guarding effect of a prenatal diagnosis. Arterial stroke occurred only in cases after BAS. As expected, neonates with CHD display slightly smaller head size and cerebral growth.
Keywords: article; atrioventricular septal defect; balloon atrioseptostomy; brain damage; brain development; brain growth; brain hemorrhage; cerebrovascular accident; clinical article; cohort analysis; congenital heart malformation; controlled study; Ebstein anomaly; echography; Fallot tetralogy; female; heart right ventricle double outlet; heart surgery; human; hypoplastic left heart syndrome; leukomalacia; male; nerve cell differentiation; newborn; preoperative evaluation; prospective study; pulmonary valve atresia; pulmonary valve stenosis; smoking

50 Years Ago in THE JOURNAL OF PEDIATRICS: Impact of Technology and Innovation on Congenital Heart Disease Survival - Paul, E.A.; Hsu, D.T. (Journal of Pediatrics, 2020)
Keywords: prostaglandin E1; arterial switch operation; article; cardiovascular risk; congenital heart disease; disease severity; heart catheterization; heart surgery; human; hypoplastic left heart syndrome; long term care; lung vein drainage anomaly; overall survival; priority journal; quality of life; surgical approach; transthoracic echocardiography

Williams Syndrome and Neonatal Cardiac Surgery for Congenital Single Ventricle - Katt, T.E.; Spicer, R.L.; Yetman, A.T.; Ibrahimiye, A.N.; Hammel, J.M.; Robinson, J.A. (JACC: Case Reports, 2020)
Williams syndrome (WS) is an arteriopathic derangement associated with supravalvular aortic stenosis and branch pulmonary stenosis. We describe double-outlet right ventricle with mitral atresia and aortic arch hypoplasia in an infant with WS. This case demonstrates the difficulty in managing patients with WS with complex cardiac defects. To our knowledge, this is the first reported single-ventricle physiology in a patient with WS. (Level of Difficulty: Advanced.)
Keywords: Ommaya reservoir; prostaglandin E1; anasarca; aorta anomaly; aortic arch hypoplasia; aortic arch surgery; artery reconstruction; article; ascites; atrioventricular septal defect; brain hemorrhage; cardiomegaly; cardiopulmonary bypass; cardiovascular system examination; case report; clinical article; clinical effectiveness; congenital heart disease; diastolic blood pressure; diastolic heart murmur; differential diagnosis; disease severity; Ebstein anomaly; echocardiography; electrocardiogram; endotracheal intubation; Fallot tetralogy; female; fetus echography; great vessels transposition; heart catheterization; heart output; heart single ventricle; heart surgery; heart valve commissurotomy; heart ventricle hypertrophy; human; hypotension; hypoxemia; image analysis; infant; intracranial pressure; lung vascular resistance; lung vein drainage anomaly; medical history; metabolic acidosis; mitral valve atresia; neonatal intensive care unit; newborn surgery; oxygen therapy; physical examination; priority journal; pulmonary artery stenosis; respiratory acidosis; supravalvular aortic stenosis; systolic blood pressure; thorax radiography; transthoracic echocardiography; tricuspid valve regurgitation; Williams Beuren syndrome

Computational modeling of a right-sided Fontan assist device: Effectiveness across patient anatomies and cannulations - Trusty, P.M.; Alan Wei, Z.; Fogel, M.A.; Maher, K.; Deshpande, S.R.; Yoganathan, A.P. (Journal of Biomechanics, 2020)
The use of mechanical circulatory support for failing Fontan patients is an area of growing interest, as the increased life expectancy of these patients continues to be accompanied by numerous end-organ complications. In vitro work has shown positive results using the CentriMag device for right-sided Fontan support, however the generalizability across various patient anatomies and cannulations is unknown. Computational simulations are first validated against in vitro modeling, then used to assess generalizability and further explore hemodynamic metrics including relative pressure changes, hepatic flow distribution, wall shear stress and power added. Computational modeling matched previous in vitro work very well, with vessel flow rates and relative average pressure change each within 1%. Positive results were seen across all patient anatomies and cannulations. On average, pressure from the vena cava to pulmonary arteries increased by 5.4 mmHg corresponding to 32 mW of power added. Hepatic flow distribution and wall shear stress were within acceptable ranges, with an average hepatic flow distribution of 47% and all patients showing ≤ 1% of the total Fontan connection surface area at a wall shear stress above 150 Pa. The positive results previously seen using CentriMag as a right-sided Fontan support device were found to be repeatable across multiple patient anatomies and cannulations. While animal models and eventual patient studies will provide further insight into the efficacy of this support strategy, our findings here suggest this method may reproduce right heart function.
Keywords: centrifugal blood pump; ventricular assist device; adolescent; adult; anatomical variation; article; blood flow velocity; blood pressure; cannulation; cava vein; child; clinical article; computer model; female; Fontan procedure; hemodynamics; human; in vitro study; liver blood flow; male; preschool child; priority journal; pulmonary artery; right sided Fontan assist device; shear stress; young adult; CentriMag

Participation in leisure activities in adolescents with congenital heart defects - Majnemer, A.; Rohlicek, C.; Dahan-Oliel, N.; Sahakian, S.; Mazer, B.; Maltais, D.B.; Schmitz, N. (Developmental Medicine and Child Neurology, 2020)
Aim: To describe leisure participation in adolescents with congenital heart defects (CHD) and identify factors associated with intensity of participation. Method: Eighty adolescents with CHD were recruited (39 males, 41 females; mean age [SD] 15y 8mo [1y 8mo] range 11y 5mo–19y 11mo) of whom 78 completed the Children’s Assessment of Participation and Enjoyment (CAPE) outcome measure of leisure participation. The measure has five subscales: recreational, active-physical, social, skill-based, and self-improvement. Associations between the CAPE and age, sex, and development were examined. Motor ability (Movement Assessment Battery for Children, Second Edition), cognition (Leiter International Performance Scale-Revised), behavior (Strengths and Difficulties Questionnaire), and motivation (Dimensions of Mastery Questionnaire) were assessed. Results: Participants exhibited impaired motor (43.5%), behavioral (23.7%), and cognitive (29.9%) development. The most intense participation was in social (mean [SD] 3.3 [0.99]) and recreational (2.9 [0.80]) activity types on the CAPE. Male sex (p<0.05) and younger age were associated with greater physical activity (<15y: 1.87; ≥15y: 1.31, p<0.05). Greater engagement in social activities was related to better cognition (r=0.28, p<0.05), higher motor function (r=0.30–0.36, p<0.01), and fewer behavioral difficulties (r=−0.32 to −0.47, p<0.01). Cognitive ability (r=0.27, p<0.05), dexterity and aiming/catching (r=0.27–0.33, p<0.05), and behavior problems (r=0.38–0.49, p=0.001) were correlated with physical activity participation. Persistence in tasks, an aspect of motivation, correlated with physical (r=0.45, p<0.001) and social activity involvement (r=0.28, p<0.05). Interpretation: Ongoing developmental impairments in adolescents with CHD are associated with decreased active-physical and social engagement, putting them at risk of poor physical and mental health. Health promotion strategies should be considered. What this paper adds: Adolescents with congenital heart defects (CHD) have limited engagement in active-physical leisure activities. Cognitive, motor, and behavioral impairments are associated with decreased participation in leisure in children with CHD. Female sex and older age are associated with less engagement in leisure. Mastery motivation correlates with participation, suggesting an avenue for intervention.
Keywords: adolescent; age; article; attention deficit disorder; child; cognitive defect; cognitive development; congenital heart malformation; educational status; Fallot tetralogy; female; hearing impairment; heart single ventricle; heart ventricle septum defect; human; learning disorder; leisure; major clinical study; male; motivation; motor dysfunction; motor performance; open heart surgery; outcome assessment; physical activity; priority journal; problem behavior; rehabilitation care; sex difference; social acceptance; social behavior; social participation

Non-Newtonian Effects on Patient-Specific Modeling of Fontan Hemodynamics - Wei, Z.; Singh-Gryzbon, S.; Trusty, P.M.; Huddleston, C.; Zhang, Y.; Fogel, M.A.; Veneziani, A.; Yoganathan, A.P. (Annals of Biomedical Engineering, 2020)
The Fontan procedure is a common palliative surgery for congenital single ventricle patients. In silico and in vitro patient-specific modeling approaches are widely utilized to investigate potential improvements of Fontan hemodynamics that are related to long-term complications. However, there is a lack of consensus regarding the use of non-Newtonian rheology, warranting a systematic investigation. This study conducted in silico patient-specific modeling for twelve Fontan patients, using a Newtonian and a non-Newtonian model for each patient. Differences were quantified by examining clinically relevant metrics: indexed power loss (iPL), indexed viscous dissipation rate (iVDR), hepatic flow distribution (HFD), and regions of low wall shear stress (AWSS). Four sets of “non-Newtonian importance factors” were calculated to explore their effectiveness in identifying the non-Newtonian effect. No statistical differences were observed in iPL, iVDR, and HFD between the two models at the population-level, but large inter-patient variations exist. Significant differences were detected regarding AWSS, and its correlations with non-Newtonian importance factors were discussed. Additionally, simulations using the non-Newtonian model were computationally faster than those using the Newtonian model. These findings distinguish good importance factors for identifying non-Newtonian rheology and encourage the use of a non-Newtonian model to assess Fontan hemodynamics.
Keywords: adolescent; article; clinical article; computational fluid dynamics; computer model; female; Fontan procedure; hemodynamic parameters; hepatic flow distribution; human; indexed power loss; indexed viscous dissipation rate; male; Newtonian model; nuclear magnetic resonance imaging; priority journal; regions of low wall shear stress

Pediatric Cardiology Specialist’s Opinions Toward the Acceptability of Comfort Care for Congenital Heart Disease - Swanson, T.M.; Patel, A.; Baxter, A.J.; Morris, S.A.; Maskatia, S.A.; Lantos, J.D. (Pediatric Cardiology, 2020)
In order to evaluate physicians’ willingness to seek legal action to mandate surgery when parents refuse surgery for various congenital heart lesions, we surveyed pediatric cardiologists and cardiovascular surgeons at 4 children’s hospitals. We asked whether physicians would support parental refusal of surgery for specific heart defects and, if not, whether they would seek legal action to mandate surgery. We then analyzed associations between physicians’ willingness to mandate surgery and national operative mortality rates for each lesion. We surveyed 126 cardiologists and 9 cardiac surgeons at four tertiary referral centers. Overall response rate was 77%. Greater than 70% of physicians would seek legal action and mandate surgery for the following lesions: ventricular septal defect, coarctation of the aorta, complete atrioventricular canal, transposition of the great arteries, tetralogy of Fallot, and unobstructed total anomalous pulmonary venous return. Surgery for all of these lesions has reported mortality rates of ' 5%. Physicians were less likely to seek legal action when parents refused surgery for Shone complex, any single ventricle lesion, or any congenital heart disease accompanied by Trisomy 13 or Trisomy 18. Among experts in pediatric cardiology, there is widespread agreement about the appropriate response to parental refusal of surgery for most congenital heart lesions, and these lesions tended to be heart defects with lower surgical mortality rates. Lesions for which there was greater consensus among experts were those with the best outcomes. There was less consensus for lesions with higher mortality rates. Such surveys, revealing disagreement among expert professionals, can provide an operational definition of the current professional “gray zone” in which parental preferences should determine treatment.
Keywords: aortic coarctation; article; atrioventricular canal; cardiac surgeon; cardiologist; congenital heart disease; consensus; controlled study; Fallot tetralogy; great vessels transposition; health survey; heart single ventricle; heart surgery; heart ventricle septum defect; human; lung vein drainage anomaly; medical care; medical expert; medicolegal aspect; mortality rate; parental attitude; patient care; pediatric cardiology; pediatric hospital; pediatric surgeon; pediatrician; physician attitude; surgical mortality; tertiary care center; treatment refusal; trisomy 13; trisomy 18

The Need to Look for Visual Deficit After Stroke in Children - Luckman, J.; Chokron, S.; Michowiz, S.; Belenky, E.; Toledano, H.; Zahavi, A.; Goldenberg-Cohen, N. (Frontiers in Neurology, 2020)
Purpose: To evaluate the role of the ophthalmologist in the management of children with arterial stroke, at presentation and during follow-up. Methods: This retrospective case series comprised children with arterial stroke who were followed for at least 12 months in a tertiary pediatric medical center in 2005–2016. Demographic data and findings on radiological neuroimaging and ophthalmological and neurological examination were retrieved from the medical files. Results: The cohort included 26 children with stroke. Underlying disorders included metabolic syndrome (n = 5, 19.2%), cardiac anomaly or Fontan repair (n = 3 each, 11.5%), vascular anomaly (n = 3, 11.5%), head trauma with traumatic dissection (n = 3, 11.5%), and hypercoagulability (n = 1, 3.8%); in eight patients (30.8%), no apparent cause was found. Eleven patients (42.3%) had a non-ophthalmological neurological deficit as a result of the stroke. Eye examination was performed in nine patients (34.6%) during follow-up. Ophthalmological manifestations included hemianopic visual field defect in seven patients (7.7%) and complete blindness and poor visual acuity in one patient each (3.8%). At the last visit, no change in visual function was detected. Conclusion: The variable etiology and presentation of pediatric stroke may mask specific visual signs. Children with arterial stroke should be referred for early ophthalmological evaluation and visual rehabilitation.
Keywords: adolescent; article; blindness; case study; cerebrovascular accident; child; child health care; childhood disease; clinical article; cohort analysis; congenital blood vessel malformation; female; Fontan procedure; head injury; heart disease; hemianopia; human; hypercoagulability; male; metabolic syndrome X; ophthalmologist; retrospective study; role playing; visual disorder; visual field defect

RVAD implantation in a Fontan patient with protein-losing enteropathy as a bridge to transplant: Prêtre modification - Moosmann, J.; Dittrich, S.; Purbojo, A.; Cesnjevar, R. (Journal of Cardiac Surgery, 2020)
Fontan patients with protein-losing enteropathy (PLE) represent poor candidates for cardiac transplantation due to end-organ injury and severely impaired clinical condition. Ventricular assist device (VAD) therapy has evolved as a promising bridge to transplant strategy improving quality of life and survival on the waiting list. However, VAD therapy for the Fontan circulation remains challenging. For Fontan patients with preserved ventricular function implantation of a right ventricular assist device (RVAD) has been described by Prêtre et al as bridge to transplant. We present the second case of RVAD support in a Fontan patient with PLE.
Keywords: dacron implant; ExCor-System; right ventricular assist device; adult; article; cardiovascular magnetic resonance; case report; clinical article; diastolic dysfunction; end to end anastomosis; female; Fontan procedure; general condition deterioration; Glenn shunt; heart catheterization; heart transplantation; heart valve replacement; hospitalization; human; palliative therapy; pleura effusion; protein losing gastroenteropathy; quality of life; young adult; ExCor-System

Neurodevelopmental outcomes at 3 years for infants with congenital heart disease and very-low birthweight - Yoshida, T.; Hiraiwa, A.; Ibuki, K.; Makimoto, M.; Inomata, S.; Tamura, K.; Kawasaki, Y.; Ozawa, S.; Hirono, K.; Ichida, F. (Pediatrics International, 2020)
Background: Both congenital heart disease (CHD) and very-low birthweight (VLBW) infants are at a very high risk of neurodevelopmental delay. We investigated neurological development at 3 years in pediatric patients with CHD after surgical intervention, those of VLBW, and healthy controls. Methods: We enrolled pediatric patients with CHD (n = 67), VLBW (n = 67), and healthy controls (n = 81). Infants with CHD were grouped into those with single ventricle and two ventricles, and infants with VLBW were grouped into those with birthweights of <1000 and 1000–1499 g. Neurodevelopmental outcomes at 3 years were evaluated using the Bayley Scales of Infant and Toddler Development, Third Edition. Results: Compared with healthy controls, a significant deficit in the language, cognition, and motor skills scores were observed in infants with CHD and VLBW. Infants with a single ventricle exhibited significantly low scores in language and gross motor skills. No statistically significant difference was observed between the birthweight groups of <1000 and 1000–1499 g. Conclusion: Neurodevelopmental outcomes for infants with both CHD and VLBW showed impairment. Notably, neurodevelopmental delays in infants with a single ventricle were remarkable. Thus, because infants with both CHD and VLBW are at high risk of neurodevelopmental disorders, periodic developmental screenings and support are warranted for these children.
Keywords: article; Bayley Scales of Infant Development; congenital heart disease; controlled study; developmental delay; disease association; female; gestational age; human; infant; language ability; major clinical study; male; motor performance; nervous system development; priority journal; risk factor; very low birth weight

Stress hyperglycemia in a pediatric emergency department setting and its relationship to the underlying disease and outcome - Levmore-Tamir, M.; Weiser, G.; Berliner, E.; Erlichman, M.; Ziv, C.A.; Levy-Khademi, F. (Israel Medical Association Journal, 2020)
Background: Stress hyperglycemia (SH) is a common finding in patients in pediatric emergency departments (PED) and has been related to increased morbidity and mortality. Objectives: To assess the incidence of SH among children visiting the PED. To identify which diseases predispose patients to SH and whether they indicate a worse outcome. Methods: Data were collected retrospectively from the medical records of all children aged 0-18 years who visited the PED during the years 2010-20 14 and who had a glucose level of > 150 mg/dl. Data collected included age, gender, weight, blood glucose level, presence or absence of a pre-existing or a new diagnosis of diabetes mellitus, and previous treatment with medications affecting blood glucose levels or with intravenous fluids containing dextrose. Data were collected regarding hospitalization, duration of hospitalization, discharge diagnosis, and survival status. Results: The study population included 1245 children with SH, which comprised 2.6% of all patients whose blood glucose level was measured in the PED during the study period. The mean age of children with SH was 49 months; 709 (56.9%) were male. The mean blood glucose level was 184 mg/dl. The rate of hospitalization was 57.8%. The mean duration of hospital stay was 5.6 days and mortality rate was 0.96%. The majority were diagnosed with a respiratory illness. Conclusions: SH is a common phenomenon among children evaluated in the PED and is associated with a high incidence of hospitalization. It may serve as an additional clinical indicator of disease severity.
Keywords: Vitros 5.1; beta adrenergic receptor stimulating agent; corticosteroid; epinephrine; glucose oxidase; abdominal pain; allergic reaction; article; asthma; autoimmune disease; bronchiolitis; burn; child; child hospitalization; dehydration; diabetes mellitus; disease severity; diseases; emergency ward; faintness; female; gastroenteritis; gastrointestinal disease; glucose blood level; heart arrhythmia; heart disease; hospital discharge; human; hyperglycemia; hypoplastic left heart syndrome; hypovolemic shock; infection; injury; kidney disease; larynx disorder; length of stay; major clinical study; male; mortality rate; neurologic disease; outcome assessment; pediatric intensive care unit; pediatric ward; pneumonia; preschool child; respiratory tract disease; resuscitation; retrospective study; seizure; thorax pain; urinary tract infection; wheezing; Vitros 5.1

Palliating Premature Infants With Obstructed Total Anomalous Pulmonary Venous Connection via Catheterization - Chamberlain, R.C.; Hill, K.D.; Fleming, G.A. (World Journal for Pediatric and Congenital Heart Surgery, 2020)
Obstructed total anomalous pulmonary venous connection (TAPVC) involves anomalous drainage of all pulmonary veins to a location other than the left atrium and typically causes significant respiratory symptoms requiring urgent surgical repair. Premature infants born with obstructed TAPVC are often not considered to be suitable surgical candidates due to their size and therefore pose a significant treatment dilemma. Catheter-based interventions provide a temporizing option for infants with obstructed TAPVC, allowing for hemodynamic stabilization and growth until surgical intervention is feasible. We describe the course of two premature infants with obstructed TAPVC who were palliated with stenting of their anomalous pulmonary veins. Both infants required repeat catheter-based intervention for recurrent stenosis and ultimately underwent successful surgical repair at an acceptable weight and corrected gestational age. We propose that a novel catheter-based approach to initial management may be a beneficial option in the premature and low-weight patient population.
Keywords: bare metal coronary stent; enoxaparin; heparin; sildenafil; article; brain hemorrhage; case report; clinical article; ductus venosus; echocardiography; follow up; Fontan procedure; heart catheterization; hemodynamics; hospitalization; human; hydrocephalus; infant; length of stay; lung artery pressure; lung vein drainage anomaly; male; oxygen saturation; percutaneous transluminal angioplasty; prematurity; priority journal; quality of life; venous pressure

Targeted metabolomic analysis of serum amino acids in the adult Fontan patient with a dominant left ventricle - Michel, M.; Dubowy, K.-O.; Entenmann, A.; Karall, D.; Adam, M.G.; Zlamy, M.; Odri Komazec, I.; Geiger, R.; Niederwanger, C.; Salvador, C.; Müller, U.; Laser, K.T.; et al. (Scientific reports, 2020)
Growing interest lies in the assessment of the metabolic status of patients with a univentricular circulation after Fontan operation, especially in changes of amino acid metabolism. Using targeted metabolomic examinations, we investigated amino acid metabolism in a homogeneous adult Fontan-patient group with a dominant left ventricle, seeking biomarker patterns that might permit better understanding of Fontan pathophysiology and early detection of subtle ventricular or circulatory dysfunction. We compared serum amino acid levels (42 analytes; AbsoluteIDQ p180 kit, Biocrates Life Sciences, Innsbruck, Austria) in 20 adult Fontan patients with a dominant left ventricle and those in age- and sex-matched biventricular controls. Serum concentrations of asymmetric dimethylarginine, methionine sulfoxide, glutamic acid, and trans-4-hydroxyproline and the methionine sulfoxide/methionine ratio (Met-SO/Met) were significantly higher and serum concentrations of asparagine, histidine, taurine, and threonine were significantly lower in patients than in controls. Met-SO/Met values exhibited a significant negative correlation with oxygen uptake during exercise. The alterations in amino acid metabolome that we found in Fontan patients suggest links between Fontan pathophysiology, altered cell energy metabolism, oxidative stress, and endothelial dysfunction like those found in biventricular patients with congestive heart failure. Studies of extended amino acid metabolism may allow better understanding of Fontan pathophysiology that will permit early detection of subtle ventricular or circulatory dysfunction in Fontan patients.
Keywords: amino acid; adverse event; blood; case control study; congenital heart malformation; coronary artery blood flow; female; Fontan procedure; heart left ventricle function; human; male; metabolism; metabolomics; oxidative stress; physiology; young adult

Transcatheter creation of bidirectional cavopulmonary connections by needle punctures in two patients - Tanase, D.; Georgiev, S.; Eicken, A.; Ewert, P. (Catheterization and Cardiovascular Interventions, 2020)
We report on two patients who received a transcatheter cavopulmonary connection by a needle puncture under deep conscious sedation. In both patients, the vessel-to-vessel connection was achieved by a venous access into the superior caval vein and direct needle puncture of the pulmonary artery. The two cavopulmonary anastomoses were held open by a covered stent and a bare-metal stent, respectively.
Keywords: Amplatzer Vascular; Amplatzer vascular plug; Andra XXL; balloon valvuloplasty catheter; bare metal stent; catheter sheath; catheter sheath; Chiba needle; goose neck snare; vascular guide wire; microcatheter; sizing balloon catheter; snare wire; Somatex; vascular guide wire; balloon valvuloplasty catheter; article; ascites; atrioventricular septal defect; cardiac imaging; case report; cavopulmonary connection; child; clinical article; comorbidity; computer assisted tomography; decision making; disease severity; Fontan procedure; heart atrium enlargement; heart atrium flutter; heart failure; hospital discharge; human; informed consent; lung vein drainage anomaly; needle biopsy; outpatient department; preschool child; pulmonary valve atresia; treatment refusal; wound closure; Amplatzer; Amplatzer Vascular; Andra XXL; Check Flo Performer; CP Stent; goose neck snare; HI Torque Floppy II; Progreat; Somatex; Z MED II

Long-term cognitive, executive, and behavioral outcomes of moderate and late preterm at school age - Jin, J.H.; Yoon, S.W.; Son, J.; Kim, S.W.; Chung, H.J. (Korean Journal of Pediatrics, 2020)
Background: There is increasing concern that moderate preterm (32–33 weeks’ gestation) and late preterm (34–36 weeks’ gestation) birth may be associated with minor neurodevelopmental problems affecting poor school performance. Purpose: We explored the cognitive function, cognitive visual function, executive function, and behavioral problems at school age in moderate to late preterm infants. Methods: Children aged 7–10 years who were born at 32+0 to 36+6 weeks of gestation and admitted to the neonatal intensive care unit from August 2006 to July 2011 at the National Health Insurance Service Ilsan Hospital were included. We excluded children with severe neurologic impairments, congenital malfor-mations, or chromosomal abnormalities. Neuropsychological assessments consisted of 5 neuropsychological tests and 3 questionnaires. Results: A total of 37 children (mean age, 9.1±1.2 years) participated. The mean gestational age at birth was 34.6±7.5 weeks, while the mean birth weight was 2,229.2±472.8 g. The mean full-scale intelligence quotient was 92.89±11.90; 24.3% scored between 70 and 85 (borderline intelligence functioning). An abnormal score was noted for at least one of the variables on the attention deficit hyperactivity disorder diagnostic system for 65% of the children. Scores below borderline function for executive quotient and memory quotient were 32.4% and 24.3%, respectively. Borderline or clinically relevant internalizing problems were noted in 13.5% on the Child Behavior Check List. There were no significant associations between perinatal factors or socioeconomic status and cognitive, visual perception, executive function, or behavior outcomes. Conclusion: Moderate to late preterm infants are at risk of developing borderline intelligence functioning and attention problems at early school age. Cognitive and executive functions that are important for academic performance must be carefully monitored and continuously followed up in moderate to late preterm infants.
Keywords: academic achievement; Apgar score; article; attention; attention deficit disorder; behavior; birth weight; child; Child Behavior Checklist; clinical article; cognition; cognitive defect; cognitive proficiency index; Down syndrome; emotionality; executive function; full scale intelligence quotient; gastrointestinal malformation; general abilities index; gestational age; human; hypoplastic left heart syndrome; hypoxic ischemic encephalopathy; intelligence quotient; male; memory; mental disease; neonatal intensive care unit; neuropsychological test; perceptual reasoning index; polydactyly; prematurity; processing speed index; questionnaire; social status; tracheoesophageal fistula; verbal comprehension index; vision; Wechsler intelligence scale for children; working memory index

Impact of Confounding on Cost, Survival, and Length-of-Stay Outcomes for Neonates with Hypoplastic Left Heart Syndrome Undergoing Stage 1 Palliation Surgery - Gong, C.L.; Song, A.Y.; Horak, R.; Friedlich, P.S.; Lakshmanan, A.; Pruetz, J.D.; Yieh, L.; Ram Kumar, S.; Williams, R.G. (Pediatric Cardiology, 2020)
The objective of this analysis was to update trends in LOS and costs by survivorship and ECMO use among neonates with hypoplastic left heart syndrome (HLHS) undergoing stage 1 palliation surgery using 2016 data from the Healthcare Cost and Utilization Project Kids’ Inpatient Database. We identified neonates ≤ 28 days old with HLHS undergoing Stage 1 surgery, defined as a Norwood procedure with modified Blalock–Taussig (BT) shunt, Sano modification, or both. Multivariable regression with year random effects was used to compare LOS and costs by hospital region, case volume, survivorship, and ECMO vs. no ECMO. An E-value analysis, an approach for conducting sensitivity analysis for unmeasured confounding, was performed to determine if unmeasured confounding contributed to the observed effects. Significant differences in total costs, LOS, and mortality were noted by hospital region, ECMO use, and sub-analyses of case volume. However, other than ECMO use and mortality, the maximum E-value confidence interval bound was 1.71, suggesting that these differences would disappear with an unmeasured confounder 1.71 times more associated with both the outcome and exposure (e.g., socioeconomic factors, environment, etc.) Our findings confirm previous literature demonstrating significant resource utilization among Norwood patients, particularly those undergoing ECMO use. Based on our E-value analysis, differences by hospital region and case volume can be explained by moderate unobserved confounding, rather than a reflection of the quality of care provided. Future analyses on surgical quality must account for unobserved factors to provide meaningful information for quality improvement.
Keywords: article; environment; extracorporeal oxygenation; female; health care cost; health care quality; health care utilization; heart surgery; human; hypoplastic left heart syndrome; length of stay; major clinical study; male; mortality; newborn; palliative therapy; social status; survival; survivorship; treatment outcome

Translation of the Frailty Paradigm from Older Adults to Children with Cardiac Disease - Panchangam, C.; White, D.A.; Goudar, S.; Birnbaum, B.; Malloy-Walton, L.; Gross-Toalson, J.; Reid, K.J.; Shirali, G.; Parthiban, A. (Pediatric Cardiology, 2020)
Children and adolescents with cardiac disease (CCD) have significant morbidity and lower quality of life. However, there are no broadly applicable tools similar to the frailty score as described in the elderly, to define functional phenotype in terms of physical capability and psychosocial wellbeing in CCD. The purpose of this study is to investigate the domains of the frailty in CCD. We prospectively recruited CCD (8–17.5 years old, 70% single ventricle, 27% heart failure, 12% pulmonary hypertension; NYHA classes I, II and III) and age and gender matched healthy controls (total n = 56; CCD n = 34, controls n = 22; age 12.6 ± 2.6 years; 39.3% female). We measured the five domains of frailty: slowness, weakness, exhaustion, body composition and physical activity using developmentally appropriate methods. Age and gender-based population norms were used to obtain Z scores and percentiles for each measurement. Two-tailed t-tests were used to compare the two groups. The CCD group performed significantly worse in all five domains of frailty compared to healthy controls. Slowness: 6-min walk test with Z score −3.9 ± 1.3 vs −1.4 ± 1.3, p < 0.001; weakness: handgrip strength percentile 18.9 ± 20.9 vs 57.9 ± 26.0, p < 0.001; exhaustion: multidimensional fatigue scale percentile 63.7 ± 13.5 vs 83.3 ± 14.4, p < 0.001; body composition: height percentile 43.4 ± 29.5 vs 71.4 ± 25.2, p < 0.001, weight percentile 46.0 ± 36.0 vs 70.9 ± 24.3, p = 0.006, BMI percentile 48.4 ± 35.5 vs 66.9 ± 24.2, p = 0.04, triceps skinfold thickness 41.0 ± 24.0 vs 54.4 ± 22.1, p = 0.04; physical activity: pediatric activity questionnaire score 2 ± 0.6 vs 2.7 ± 0.6, p < 0.001. The domains of frailty can be quantified in children using developmentally appropriate methods. CCD differ significantly from controls in all five domains, supporting the concept of quantifying the domains of frailty. Larger longitudinal studies are needed to study frailty in CCD and examine if it predicts adverse health outcomes. Clinical Trial Registration: The ClinicalTrials.gov identification number is NCT02999438. https://clinicaltrials.gov/ct2/show/NCT02999438.
Keywords: NCT02999438; accelerometer; ActiGraph wGT3X-BT; personal digital assistant; adolescent; article; body composition; child; controlled study; female; frailty; grip strength; hand grip; health insurance; heart disease; heart failure; household; human; major clinical study; male; multidimensional fatigue scale; New York Heart Association class; physical activity; prediction; prospective study; psychosocial care; pulmonary hypertension; quality of life; rating scale; six minute walk test; translational research; ActiGraph wGT3X-BT

Reduction of Inflammation by High-Dose Methylprednisolone Does not Attenuate Oxidative Stress in Children Undergoing Bidirectional Glenn Procedure With or Without Aortic Arch or Pulmonary Arterial Repair - Keski-Nisula, J.; Arvola, O.; Jahnukainen, T.; Andersson, S.; Pesonen, E. (Journal of Cardiothoracic and Vascular Anesthesia, 2020)
Objective: Corticosteroids attenuate an inflammatory reaction in pediatric heart surgery. Inflammation is a source of free oxygen radicals. Children with a cyanotic heart defect are prone to increased radical stress during heart surgery. The authors hypothesized that high-dose methylprednisolone reduces inflammatory reaction and thereby also oxidative stress in infants with a univentricular heart defect undergoing the bidirectional Glenn procedure. Design: A double-blind, placebo-controlled, randomized clinical trial. Setting: Operating room and pediatric intensive care unit of a university hospital. Participants: The study comprised 29 infants undergoing the bidirectional Glenn procedure with or without aortic arch or pulmonary arterial repair. Interventions: After anesthesia induction, the patients received intravenously either 30 mg/kg of methylprednisolone (n = 15) or the same volume of saline as placebo (n = 14). Measurements and Main Results: Plasma interleukin-6, interleukin-8, interleukin-10 (biomarkers of inflammation), and 8-hydroxydeoxyguanosine concentrations (a biomarker of oxidative stress) were measured at the following 4 time points: preoperatively, during cardiopulmonary bypass, after protamine administration, and 6 hours postoperatively. The study parameters did not differ between the study groups preoperatively. Methylprednisolone reduced the proinflammatory cytokines interleukin-6 and interleukin-8 and increased the anti-inflammatory cytokine interleukin-10 postoperatively. Despite reduced inflammation, there were no differences in 8-hydroxydeoxyguanosine between the methylprednisolone and placebo groups. Conclusions: The proinflammatory reaction and increase in free radical stress were not interrelated during congenital heart surgery in cyanotic infants with a univentricular heart defect undergoing the bidirectional Glenn procedure. High-dose methylprednisolone was ineffective in attenuating free radical stress.
Keywords: EudraCT2008-007413-76; 8 hydroxydeoxyguanosine; biological marker; free radical; interleukin 10; interleukin 6; interleukin 8; methylprednisolone; placebo; sodium chloride; antiinflammatory activity; aortic arch surgery; artery reconstruction; article; blood level; clinical article; clinical outcome; controlled study; cytokine production; double blind procedure; drug effect; drug mechanism; drug megadose; female; Glenn shunt; heart single ventricle; human; infant; inflammation; male; oxidative stress; palliative therapy; pediatric intensive care unit; postoperative period; preoperative period; priority journal; pulmonary artery repair; randomized controlled trial; university hospital

Longitudinal study of anthropometry in Fontan survivors: Pediatric Heart Network Fontan study - Lambert, L.M.; McCrindle, B.W.; Pemberton, V.L.; Hollenbeck-Pringle, D.; Atz, A.M.; Ravishankar, C.; Campbell, M.J.; Dunbar-Masterson, C.; Uzark, K.; Rolland, M.; Trachtenberg, F.L.; Menon, S.C. (American Heart Journal, 2020)
Background: Growth abnormalities in single-ventricle survivors may reduce quality of life (QoL) and exercise capacity. Methods: This multicenter, longitudinal analysis evaluated changes in height and body mass index (BMI) compared to population norms and their relationship to mortality, ventricular morphology, QoL, and exercise capacity in the Pediatric Heart Network Fontan studies. Results: Fontan 1 (F1) included 546 participants (12 ± 3.4 years); Fontan 2 (F2), 427 (19 ± 3.4 years); and Fontan 3 (F3), 362 (21 ± 3.5 years), with ~60% male at each time point. Height z-score was −0.67 ± −1.27, −0.60 ± 1.34, and− 0.43 ± 1.14 at F1-F3, lower compared to norms at all time points (P ≤ .001). BMI z-score was similar to population norms. Compared to survivors, participants who died had lower height z-score (P ≤ .001). Participants with dominant right ventricle (n = 112) had lower height z-score (P ≤ .004) compared to dominant left (n = 186) or mixed (n = 64) ventricular morphologies. Higher height z-score was associated with higher Pediatric Quality of Life Inventory for the total score (slope = 2.82 ± 0.52; P ≤ .001). Increase in height z-score (F1 to F3) was associated with increased oxygen consumption (slope = 2.61 ± 1.08; P = .02), whereas, for participants >20 years old, an increase in BMI (F1 to F3) was associated with a decrease in oxygen consumption (slope = −1.25 ± 0.33; P ≤ .001). Conclusions: Fontan survivors, especially those with right ventricular morphology, are shorter when compared to the normal population but have similar BMI. Shorter stature was associated with worse survival. An increase in height z-score over the course of the study was associated with better QoL and exercise capacity; an increase in BMI was associated with worse exercise capacity.
Keywords: anthropometry; article; body height; body mass; body weight; child; controlled study; exercise; female; heart right ventricle; human; longitudinal study; major clinical study; male; mortality; multicenter study; oxygen consumption; Pediatric Quality of Life Inventory; quality of life; survivor

Health related quality of life in children with congenital heart disease that undergo cardiac surgery during their first year of life - Saavedra, M.J.; Eymann, A.; Pérez, L.; Busaniche, J.; Nápoli, N.; Marantz, P.; Llera, J. (Archivos Argentinos de Pediatria, 2020)
Introduction. Advances in diagnostic methods, surgical techniques and postoperative intensive care have significantly increased the survival rates for children with congenital heart disease. In this context, long term sequelae acquired greater relevance. Health-related quality of life (HRQOL) is a concept that helps to measure the impact of chronic diseases. The purpose of the current study was to describe HRQOL in children with congenital heart disease that undergo cardiac surgery during their first year of life. Methods. A cross-sectional observational study was conducted between August 2017 and December 2018 at a University General Hospital. PedsQL 4.0 Generic Core Scales were used. Children with congenital heart disease between 2 and 4 years old who had cardiac surgery during their first year of life and healthy children were included. Scores were compared with T-test or Wilcoxon according to the observed distribution. p value < 0.05 was considered significant. Results. A total of 31 children with congenital heart disease (26 % with a single ventricle) and 62 healthy children were enrolled. The first surgery was in the neonatal period in 61.3 %. Our study showed no statistical differences (p = 0.10) between HRQOL Total Scale Score of children with congenital heart disease compared to healthy children. However, lower scores were observed with statistically significant differences in social (p = 0.0092) and school (p = 0.0001) scales. Conclusions. Our cohort of children diagnosed with congenital heart disease has a global quality of life comparable with healthy children except in social and school functioning scales.
Keywords: article; child; clinical article; congenital heart disease; controlled study; cross-sectional study; heart surgery; human; newborn period; observational study; pediatric patient; preschool child; quality of life; school; scoring system; social aspect

Management of Hyperactive Delirium in the Pediatric Intensive Care Unit: Case Series of Three Young Children - Jesus, A.O.; Jones, L.; Linares, R.; Buck, M.L.; Frank, D.U. (Journal of Pediatric Intensive Care, 2020)
Children in the intensive care unit (ICU) are at high risk of developing delirium, given their underlying disease processes, the adverse effects of treatments and medications, and the stressful, abnormal environment. If prevention and nonpharmacologic measures to treat delirium are unsuccessful, atypical antipsychotics are considered, although they are not approved by Food and Drug Administration for the treatment of pediatric delirium and could have significant adverse side effects. This case report presents three pediatric patients with hyperactive ICU delirium that risked life-Threating complications who were successfully treated with short courses of atypical antipsychotic medications.
Keywords: wrist restraint; atypical antipsychotic agent; cisatracurium; clonidine; dexmedetomidine; fentanyl; gabapentin; haloperidol; hydromorphone; ketamine; lorazepam; melatonin; methadone; midazolam; morphine; neuromuscular blocking agent; pentobarbital; risperidone; steroid; apathy; article; case report; child; clinical article; continuous infusion; delirium; drug substitution; drug withdrawal; evening dosage; female; heart catheterization; human; hypoplastic left heart syndrome; infant; low drug dose; male; pediatric intensive care unit; priority journal; QT prolongation; somnolence; syndrome CHARGE; tachyphylaxis

N-terminal pro-brain natriuretic peptide serum levels reflect attrition of the Fontan circulation - Wolff, D.; Van Melle, J.P.; Willems, T.P.; Bartelds, B.; Ploegstra, M.-J.; Hillege, H.; Ebels, T.; Berger, R.M.F. (Cardiology in the Young, 2020)
Objective: N-terminal pro-brain natriuretic peptide has an established role in the diagnosis and prognosis of heart failure. In Fontan patients, this peptide is often increased, but its diagnostic value in this particular non-physiologic, univentricular circulation is unclear. We investigated whether N-terminal pro-brain natriuretic peptide represents ventricular function or other key variables in Fontan patients.Methods and results: Ninety-five consecutive Fontan patients ≥10 years old who attended the outpatient clinic of the Center for Congenital Heart Diseases in 2012-2013 were included. Time since Fontan completion was 16 ± 9 years. Median N-terminal pro-brain natriuretic peptide was 114 (61-264) ng/l and was higher than gender-and age-dependent normal values in 54% of the patients. Peptide Z-scores were higher in patients in NYHA class III/IV compared to those in class I/II, but did not correlate with ventricular function assessed by MRI and echocardiography, nor with peak exercise capacity. Instead, peptide Z-scores significantly correlated with follow-up duration after Fontan completion (p < 0.001), right ventricular morphology (p = 0.004), indexed ventricular mass (p = 0.001), and inferior caval vein diameter (p < 0.001) (adjusted R= 0.615).Conclusions: N-terminal pro-brain natriuretic peptide levels in Fontan patients correlate with functional class, but do not necessarily indicate ventricular dysfunction. Increased peptide levels were associated with a longer existence of the Fontan circulation, morphologic ventricular characteristics, and signs of increased systemic venous congestion. Since the latter are known to be key determinants of the performance of the Fontan circulation, these findings suggest increase in N-terminal pro-brain natriuretic peptide levels to indicate attrition of the Fontan circulation, independent of ventricular function.
Keywords: nuclear magnetic resonance scanner; amino terminal pro brain natriuretic peptide; adolescent; adult; aging; article; child; comparative study; cross-sectional study; echocardiography; exercise; female; follow up; Fontan procedure; heart left ventricle mass; heart right ventricle; heart ventricle function; human; inferior cava vein; major clinical study; male; New York Heart Association class; nuclear magnetic resonance imaging; outpatient department; patient attendance; Peptide Z score; protein analysis; protein blood level; school child; scoring system; sex ratio; vein diameter; venous congestion

Impaired histomorphology might provoke cell cycle regulators alteration in thymus of children with various congenital heart defects - Mestanova, V.; Varga, I.; Adamkov, M. (Medical Hypotheses, 2020)
Thymus, as a primary site of appropriate adaptive immunity formation, is an essential organ in face of a self-tolerance as well as a potential menace from impairment of body integrity. Due to vital selection processes during differentiation and maturation of T lymphocytes, control over cell survival and programmed cell death must be orchestrated in detail. Indeed, thymus is highly sensitive to wide spectrum of stressors that initiate acute structural changes. Hypoxia, one of the most common complications in congenital heart defects (CHDs) patients, provokes stress-induced thymus involution. Disrupted embryolonic development of thymus in association with congenital heart defects, may negatively affect physiological immune mechanisms. We propose that detailed analysis of thymic morphology could critically contribute to unveil the pathophysiology of diseases associated with disrupted adaptive immunity in children with heterogeneous congenital heart diseases.
Keywords: cytokeratin AE1; cytokeratin AE3; Ki 67 antigen; protein bcl 2; protein p53; survivin; adaptive immunity; aorta anomaly; apoptosis; article; CD4+ T lymphocyte; CD8+ T lymphocyte; cell maturation; cell survival; congenital aortic atresia; disease severity; epithelium cell; Fallot tetralogy; G2 phase cell cycle checkpoint; great vessels transposition; heart right ventricle double outlet; heart ventricle septum defect; human; hypoplastic left heart syndrome; hypoxia; immunohistochemistry; macrophage; medullary thymic epithelial cell; pathophysiology; protein expression; physiological stress; thymocyte; thymus; ventricular septal defect type 1; ventricular septal defect type 4

A transition clinic intervention to improve follow-up rates in adolescents and young adults with congenital heart disease - Gaydos, S.S.; Chowdhury, S.M.; Judd, R.N.; McHugh, K.E. (Cardiology in the Young, 2020)
Background: Children with congenital heart disease (CHD) require lifelong cardiology follow-up. Many experience gaps in care around the age of transition to adult-oriented care with associated comorbidity. We describe the impact of a clinic-based intervention on follow-up rates in this high-risk population.Methods: Patients ≥11 years seen in a paediatric outpatient CHD Transition Clinic completed self-assessment questionnaires, underwent focused teaching, and were followed on a clinic registry with assessment of care continuation. The cohort lost to follow-up rate, defined as absence from care at least 6 months beyond the recommended timeframe, was compared with a control group. Secondary outcomes included questionnaire scores and adult cardiology referral trends.Results: Over 26 months, 53 participants completed an initial Transition Clinic visit; 43% (23/53) underwent a second visit. Median participant age was 18.0 years (interquartile range 16.0, 22.0). The cohort's lost to follow-up rate was 7.3%, which was significantly lower than the control rate (25.9%, p < 0.01). Multivariable regression analyses demonstrated clinic participation as the only factor independently associated with follow-up rates (p = 0.048). Transition readiness was associated with older age (p = 0.01) but not sex, univentricular heart, interventional history, or surgical complexity. One-third of adult participants transferred to adult care.Conclusions: A CHD Transition Clinic intervention can improve follow-up rates in adolescents and young adults. Age is an important factor in transition readiness, and retention of adults in paediatric care appears multi-factorial. We postulate that serial assessments of self-management, focused education, and registry utilisation may improve patient outcomes by reducing lapses in care.
Keywords: adolescent; adult; age distribution; article; case control study; child; cohort analysis; congenital heart disease; controlled study; female; follow up; heart single ventricle; high risk population; human; major clinical study; male; medical history; outcome assessment; outpatient care; patient education; patient referral; quality of life; register; retention in care; retrospective study; self evaluation; sex difference; transition to adult care; transitional care; trend study; young adult

Appropriate heart rate during exercise in Fontan patients - Hedlund, E.R.; Söderström, L.; Lundell, B. (Cardiology in the Young, 2020)
Objective: To evaluate heart rate against workload and oxygen consumption during exercise in Fontan patients.Method: Fontan patients (n = 27) and healthy controls (n = 25) underwent cardiopulmonary exercise testing with linear increase of load. Heart rate and oxygen uptake were measured during tests. Heart rate recovery was recorded for 10 minutes.Results: Heart rate at midpoint (140 ± 14 versus 153 ± 11, p < 0.001) and at maximal effort (171 ± 14 versus 191 ± 10 beats per minute, p < 0.001) of test was lower for patients than controls. Heart rate recovery was similar between groups. Heart rate in relation to workload was higher for patients than controls both at midpoint and maximal effort. Heart rate in relation to oxygen uptake was similar between groups throughout test. Oxygen pulse, an indirect surrogate measure of stroke volume, was reduced at maximal effort in patients compared to controls (6.6 ± 1.1 versus 7.5 ± 1.4 ml·beat-1·m-2, p < 0.05) and increased significantly less from midpoint to maximal effort for patients than controls (p < 0.05).Conclusions: Heart rate is increased in relation to workload in Fontan patients compared with controls. At higher loads, Fontan patients seem to have reduced heart rate and smaller increase in oxygen pulse, which may be explained by inability to further increase stroke volume and cardiac output. Reduced ability to increase or maintain stroke volume at higher heart rates may be an important limiting factor for maximal cardiac output, oxygen uptake, and physical performance.
Keywords: bicycle ergometer; Ergomedic 839E; Exercise AB; GE CASE; captopril; enalapril; adolescent; article; cardiopulmonary exercise test; clinical article; controlled study; female; Fontan procedure; heart output; heart rate; heart stroke volume; human; lung gas exchange; male; oxygen consumption; prescription; pulse oximetry; self report; Ergomedic 839E; Exercise AB; GE CASE

Brief version of the coping health inventory for parents (CHIP) among family caregivers of children with chronic diseases - Toledano-Toledano, F.; Moral De La Rubia, J.; McCubbin, L.D.; Cauley, B.; Luna, D. (Health and Quality of Life Outcomes, 2020)
Background: The Coping Health Inventory for Parents (CHIP) has demonstrated good psychometric properties in several language forms and has been used to assess the coping behaviors of families facing disease. However, the CHIP has not been validated in Mexico among families of children with chronic conditions, where it could be useful for research and intervention. The objectives of this instrumental study were to obtain a version of the CHIP for the Spanish language in Mexico, establish the factor structure of the Mexican version of the CHIP, probe its internal consistency reliability, and assess its concurrent construct validity. Methods: A nonprobability sample of 405 family caregivers of children with chronic diseases responded to a battery of measurement instruments that included the CHIP, the Beck Anxiety Inventory, and the Beck Depression Inventory. The sample was randomly divided into two parts. In one subsample (190 participants), an exploratory factor analysis was performed using a principal component analysis and oblique rotation. In the second subsample (215 participants), a confirmatory factor analysis was performed using maximum likelihood estimation. Results: The scale was reduced to 16 items (CHIP-16) with factorial loads greater than.50. The empirical criteria used to determine the number of factors converged on the following five factors: belief and trust (McDonald ω =.85), spouse/partner relationship (ω =.79), home care (ω =.77), family involvement (ω =.75), and security/stability (ω =.79). The overall internal consistency was good (ω =.88). The five-factor model showed acceptable fit indices and high parsimony. The mean CHIP-16 scores and the Spouse/partner relationship scores among the caregivers with anxiety were greater than those among the caregivers without anxiety. The mean home-care scores among the women were greater than those among men. Conclusions: The 16-item version of the CHIP showed good internal consistency and construct validity; thus, the CHIP-16 is a useful instrument for measuring and assessing coping in family caregivers of children with chronic diseases.
Keywords: adult; article; asthma; Beck Anxiety Inventory; Beck Depression Inventory; caregiver; child; chronic disease; concurrent validity; confirmatory factor analysis; congenital heart malformation; construct validity; controlled study; Coping Health Inventory for Parents; cystic fibrosis; Down syndrome; end stage renal disease; exploratory factor analysis; female; human; Human immunodeficiency virus infection; internal consistency; major clinical study; male; malignant neoplasm; maximum likelihood method; nephrotic syndrome; oblique rotation; pediatric patient; principal component analysis; psychometry; reliability; school child; Spanish (language); tricuspid valve atresia

Surgical palliation or primary transplantation for aortic valve atresia - Stackhouse, K.A.; McCrindle, B.W.; Blackstone, E.H.; Rajeswaran, J.; Kirklin, J.K.; Bailey, L.L.; Jacobs, M.L.; Tchervenkov, C.I.; Jacobs, J.P.; Pettersson, G.B. (Journal of Thoracic and Cardiovascular Surgery, 2020)
Objective: The study objective was to describe the surgical pathway progression through adolescence of an inception cohort of neonates with aortic valve atresia managed initially with surgical palliation or primary transplantation, comparing survival and self-reported health-related quality of life. Methods: From 1994 to 2000, 565 neonates with aortic atresia were admitted to 26 Congenital Heart Surgeons' Society hospitals and followed annually for vital status. Initial management included surgical palliation (n = 453) and primary cardiac transplantation (n = 68). PedsQL health-related quality of life questionnaires were sent cross-sectionally to a subgroup of 198 patients alive at previous follow-up, with 80 responses. Results: Risk of death was initially high for both treatment strategies. However, compared with initial surgical palliation, survival with primary transplantation, including wait-list mortality, was greater and persisted long-term (65% vs 40% at 15 years; P =.002). Survival after secondary transplantation (48% at 9 years) was lower than after primary transplantation (74%). Health-related quality of life total score was lower overall than that of the general adolescent population (71 ± 16 vs 84 ± 13; P =.0001; normal = 100), but similar to that of adolescents with chronic diseases. It was similar in the surgical palliation and primary transplantation groups (70 ± 16 vs 75 ± 15; P =.3). Patients who received surgical palliation reported more symptoms (76 ± 15 vs 63 ± 18; P =.02). Conclusions: Patients receiving primary heart transplantation for aortic atresia in 1994 to 2000 experienced better survival, fewer symptoms, and equivalent quality of life compared with those undergoing initial surgical palliation. Notwithstanding the limited availability of neonatal and infant donor hearts, primary transplantation may be considered for those neonates with risk factors predictive of exceptionally poor survival after surgical palliation.
Keywords: adolescent; aorta valve atresia; aortic valve disease; article; chronic disease; controlled study; cross-sectional study; female; follow up; Fontan procedure; heart atrium septum defect; heart transplantation; heart ventricle septum defect; human; major clinical study; male; mitral valve atresia; newborn; Norwood procedure; palliative therapy; Pediatric Quality of Life Inventory; priority journal; pulmonary valve insufficiency; quality of life; survival; tricuspid valve regurgitation

Efficacy of phosphodiesterase type 5 inhibitors in univentricular congenital heart disease: the SV-INHIBITION study design - Amedro, P.; Gavotto, A.; Abassi, H.; Picot, M.-C.; Matecki, S.; Malekzadeh-Milani, S.; Levy, M.; Ladouceur, M.; Ovaert, C.; Aldebert, P.; Thambo, J.-B.; Fraisse, A.; et al. (ESC Heart Failure, 2020)
Aims: In univentricular hearts, selective lung vasodilators such as phosphodiesterase type 5 (PDE5) inhibitors would decrease pulmonary resistance and improve exercise tolerance. However, the level of evidence for the use of PDE5 inhibitors in patients with a single ventricle (SV) remains limited. We present the SV-INHIBITION study rationale, design, and methods. Methods and results: The SV-INHIBITION trial is a nationwide multicentre, randomized, double blind, placebo-controlled, Phase III study, aiming to evaluate the efficacy of sildenafil on the ventilatory efficiency during exercise, in teenagers and adult patients (>15 years old) with an SV. Patients with a mean pulmonary arterial pressure >15 mmHg and a trans-pulmonary gradient >5 mmHg, measured by cardiac catheterization, will be eligible. The primary outcome is the variation of the VE/VCO2 slope, measured by a cardiopulmonary exercise test, between baseline and 6 months of treatment. A total of 50 patients are required to observe a decrease of 5 ± 5 points in the VE/VCO2 slope, with a power of 90% and an alpha risk of 5%. The secondary outcomes are clinical outcomes, oxygen saturation, 6 min walk test, SV function, NT-proBNP, peak VO2, stroke volume, mean pulmonary arterial pressure, trans-pulmonary gradient, SF36 quality of life score, safety, and acceptability. Conclusions: The SV-INHIBITION study aims to answer the question whether PDE5 inhibitors should be prescribed in patients with an SV. This trial has been built focusing on the three levels of research defined by the World Health Organization: disability (exercise tolerance), deficit (SV function), and handicap (quality of life).
Keywords: NCT03153137; amino terminal pro brain natriuretic peptide; carbon dioxide; oxygen; phosphodiesterase V inhibitor; placebo; sildenafil; adolescent; adult; arterial oxygen saturation; article; cardiopulmonary exercise test; clinical article; clinical outcome; congenital heart disease; controlled study; double blind procedure; drug efficacy; drug safety; drug screening; heart catheterization; heart single ventricle; heart stroke volume; human; human cell; lung artery pressure; lung ventilation; mean arterial pressure; multicenter study; outcome assessment; parallel design; phase 3 clinical trial; pressure gradient; priority journal; pulmonary artery occlusion pressure; quality of life; randomized controlled trial; respiratory tract parameters; scoring system; Short Form 36; six minute walk test; World Health Organization

Prevalence, features and predictive factors of liver nodules in Fontan surgery patients: The VALDIG Fonliver prospective cohort - Téllez, L.; Rodríguez de Santiago, E.; Minguez, B.; Payance, A.; Clemente, A.; Baiges, A.; Morales-Arraez, D.; La Mura, V.; Llop, E.; Garrido, E.; Garrido-Lestache, E.; Tasayco, S.; et al. (Journal of Hepatology, 2020)
Background & Aims: Fontan surgery is used to treat a variety of congenital heart malformations, and may lead to advanced chronic liver disease in the long-term. This study examines the prevalence, characteristics and predictors of liver nodules in patients following Fontan surgery. Methods: This was a prospective, cross-sectional, observational study conducted at 8 European centres. Consecutive patients who had undergone Fontan surgery underwent blood tests, abdominal ultrasonography (US), transient elastography (Fibroscan®), echocardiography, haemodynamic assessments, and abdominal MRI/CT scan. The primary outcome measure was liver nodules detected in the MRI/CT scan. Predictors of liver nodules were identified by multivariate logistic regression. Results: One hundred and fifty-two patients were enrolled (mean age 27.3 years). The mean time elapsed from surgery to inclusion was 18.3 years. Liver nodule prevalences were 29.6% (95% CI 23–37%) on US and 47.7% (95% CI 39–56%) on MRI/CT. Nodules were usually hyperechoic (76.5%), round-shaped (>80%), hyperenhancing in the arterial phase (92%) and located in the liver periphery (75%). The sensitivity and specificity of US were 50% (95% CI 38–62%) and 85.3% (95% CI 75–92%), respectively. Inter-imaging test agreement was low (adjusted kappa: 0.34). In the multivariate analysis, time since surgery >10 years was the single independent predictor of liver nodules (odds ratio 4.18; p = 0.040). Hepatocellular carcinoma was histologically diagnosed in 2 of the 8 patients with hypervascular liver nodules displaying washout. Conclusion: While liver nodules are frequent in Fontan patients, they may go unnoticed in US. Liver nodules are usually hyperechoic, hypervascular and predominantly peripheral. This population is at risk of hepatocellular carcinoma, the diagnosis of which requires confirmatory biopsy. Lay summary: Fontan surgery is the standard of care for many patients with univentricular congenital cardiopathies. Recent advances have improved the survival of Fontan patients, and nowadays most of them reach adulthood. In this setting, Fontan-associated liver disease (FALD) is increasingly recognised, and has become a significant prognostic factor. Liver nodules are considered a component of FALD yet their prevalence, imaging features and predictors have hardly been evaluated. In this study, we observed that liver nodules are frequent, typically hyperechoic, hypervascular and predominantly peripheral in patients with FALD. This population is at risk of hepatocellular carcinoma, the diagnosis of which must be confirmed by biopsy.
Keywords: adolescent; adult; alcohol consumption; article; ascites; atrioventricular septal defect; body mass; chronic liver disease; congenital heart malformation; criss cross atrioventricular relationship; cross-sectional study; diagnostic accuracy; echocardiography; echography; female; Fontan procedure; gallstone; hemodynamics; human; liver biopsy; liver cell carcinoma; liver nodule; major clinical study; male; mitral valve atresia; nuclear magnetic resonance imaging; observational study; priority journal; prospective study; protein losing gastroenteropathy; pulmonary valve atresia; splenomegaly; surgical patient; transient elastography; tricuspid valve atresia; x-ray computed tomography; young adult

Risk Factors for Prolonged Mechanical Ventilation After Total Cavopulmonary Connection Surgery: 8 Years of Experience at Fuwai Hospital - Luo, Q.; Su, Z.; Jia, Y.; Liu, Y.; Wang, H.; Zhang, L.; Li, Y.; Wu, X.; Liu, Q.; Yan, F. (Journal of Cardiothoracic and Vascular Anesthesia, 2020)
Objective: Prolonged mechanical ventilation (PMV) is closely associated with higher morbidity and mortality after total cavopulmonary surgery. The aim of the present study was to identify the clinical risk factors for PMV. Design: A retrospective case-control study. Setting: Fuwai Hospital. Participants: The study comprised 504 patients who underwent total cavopulmonary surgery from 2010 to 2018. Interventions: None. Measurements and Main Results: The definition of PMV was derived from the Cox regression model for predicting postoperative length of hospital stay. Least absolute shrinkage and selection operator regression, logistic regression, and Cox regression were applied to identify predictors for PMV. Patients with mechanical ventilation time >9 hours were identified as having PMV. Independent predictors of PMV included age, intraoperative maximum vasoactive-inotropic score, minimal temperature during cardiopulmonary bypass, postoperative prothrombin time, alkaline phosphatase and total bilirubin levels, and postoperative fluid balance. These predictors also were achieved in the Cox regression for predicting the duration of mechanical ventilation. Patients with PMV were associated with increased blood transfusions, more consumption of vasopressin and antipulmonary hypertension medication, higher incidence of reintubation, more renal replacement treatment, longer intensive care unit stay, greater hospitalization costs, and more specialist visits. Conclusions: Age at surgery, maximal vasoactive-inotropic score and minimal temperature during cardiopulmonary bypass, postoperative prothrombin time, alkaline phosphatase and total bilirubin levels, and postoperative fluid balance were demonstrated to be independent predictors of PMV. Adopting a comprehensive strategy of perioperative management that targets the identified risk factors might significantly lower the risk of PMV and improve in-hospital outcomes, and furthermore, patients with PMV might need more specialist visits.
Keywords: alkaline phosphatase; bilirubin; fresh frozen plasma; inotropic agent; levosimendan; vasopressin; article; artificial ventilation; atrioventricular septal defect; blood transfusion; body surface; cardiopulmonary bypass; case control study; cavopulmonary connection; child; controlled study; erythrocyte transfusion; estimated glomerular filtration rate; fluid balance; follow up; health care cost; heart ejection fraction; heart left ventricle; heart left ventricle enddiastolic diameter; heart right ventricle; heart right ventricle double outlet; heterotaxy syndrome; hospital mortality; hospitalization cost; human; hypervolemia; intensive care unit; length of stay; lung artery pressure; major clinical study; postoperative period; preoperative evaluation; preschool child; priority journal; prothrombin time; pulmonary hypertension; pulmonary valve atresia; renal replacement therapy; retrospective study; risk factor; risk reduction; thrombocyte transfusion; total cavopulmonary connection surgery; treatment duration; tricuspid valve atresia

Biallelic variants in KYNU cause a multisystemic syndrome with hand hyperphalangism - Ehmke, N.; Cusmano-Ozog, K.; Koenig, R.; Holtgrewe, M.; Nur, B.; Mihci, E.; Babcock, H.; Gonzaga-Jauregui, C.; Overton, J.D.; Xiao, J.; Martinez, A.F.; Muenke, M.; et al. (Bone, 2020)
Catel-Manzke syndrome is characterized by the combination of Pierre Robin sequence and radial deviation, shortening as well as clinodactyly of the index fingers, due to an accessory ossification center. Mutations in TGDS have been identified as one cause of Catel-Manzke syndrome, but cannot be found as causative in every patient with the clinical diagnosis. We performed a chromosome microarray and/or exome sequencing in three patients with hand hyperphalangism, heart defect, short stature, and mild to severe developmental delay, all of whom were initially given a clinical diagnosis of Catel-Manzke syndrome. In one patient, we detected a large deletion of exons 1–8 and the missense variant c.1282C > T (p.Arg428Trp) in KYNU (NM_003937.2), whereas homozygous missense variants in KYNU were found in the other two patients (c.989G > A (p.Arg330Gln) and c.326G > C (p.Trp109Ser)). Plasma and urine metabolomic analysis of two patients indicated a block along the tryptophan catabolic pathway and urine organic acid analysis showed excretion of xanthurenic acid. Biallelic loss-of-function mutations in KYNU were recently described as a cause of NAD deficiency with vertebral, cardiac, renal and limb defects; however, no hand hyperphalangism was described in those patients, and Catel-Manzke syndrome was not discussed as a differential diagnosis. In conclusion, we present unrelated patients identified with biallelic variants in KYNU leading to kynureninase deficiency and xanthurenic aciduria as a very likely cause of their hyperphalangism, heart defect, short stature, and developmental delay. We suggest performance of urine organic acid analysis in patients with suspected Catel-Manzke syndrome, particularly in those with cardiac or vertebral defects or without mutations in TGDS.
Keywords: computed tomography scanner; extracorporeal membrane oxygenation device; percutaneous endoscopic gastrostomy tube; carboxylic acid; kynureninase; levetiracetam; tryptophan; valproic acid; xanthurenic acid; aciduria; adolescent; amniocentesis; article; attention deficit disorder; blood level; bradycardia; brain radiography; Caribbean (person); case report; catabolism; Catel Manzke syndrome; child; chromosome analysis; clinical article; clinical feature; clinodactyly; cochlea hypoplasia; cognitive defect; complete heart block; computer assisted tomography; developmental delay; disease severity; dysostosis; echography; electroencephalogram; enzyme deficiency; evoked brain stem auditory response; exon; extracorporeal oxygenation; face dysmorphia; Fallot tetralogy; family history; feeding difficulty; female; Fontan procedure; gene deletion; genetic variability; gestational age; hand hyperphalangism; hand malformation; hand radiography; heart atrium septum defect; heart disease; heart failure; heart ventricle septum defect; hepatomegaly; homozygosity; human; hypoplasia; hypoplastic left heart syndrome; joint laxity; kidney agenesis; KYNU gene; learning disorder; Lennox Gastaut syndrome; loss of function mutation; male; medical history; mental performance; metabolome; metabolomics; microarray analysis; microcephaly; missense mutation; motor dysfunction; muscle hypotonia; occupational therapy; patient referral; perception deafness; physical examination; physiotherapy; renography; retrognathia; scoliosis; short stature; speech delay; speech therapy; systemic disease; tonic seizure; Turk (people); urine level; vaginal delivery; whole exome sequencing; Wide Range Achievement Test; X ray; xanthurenic aciduria

Heart rate variability is depressed in the early transitional period for newborns with complex congenital heart disease - Mulkey, S.B.; Govindan, R.; Metzler, M.; Swisher, C.B.; Hitchings, L.; Wang, Y.; Baker, R.; Larry Maxwell, G.; Krishnan, A.; du Plessis, A.J. (Clinical Autonomic Research, 2020)
Purpose: To compare early changes in autonomic nervous system (ANS) tone between newborns with complex congenital heart disease (CHD) and newborns without CHD. Methods: We performed a case–control study of heart rate variability (HRV) in newborns with complex CHD [transposition of the great arteries (TGA) or hypoplastic left heart syndrome (HLHS)] and low-risk control newborns without CHD. Cases with CHD were admitted following birth to a pediatric cardiac intensive care unit and had archived continuous ECG data. Control infants were prospectively enrolled at birth. ECG data in cases and controls were analyzed for HRV in the time and frequency domains at 24 h of age. We analyzed the following HRV metrics: alpha short (αs), alpha long (αL), root mean square short and long (RMSs and RMSL), low-frequency (LF) power, normalized LF (nLF), high-frequency (HF) power, and normalized HF (nHF). We used ANOVA to compare HRV metrics between groups and to control for medication exposures. Results: HRV data from 57 infants with CHD (TGA, n = 33 and HLHS, n = 24) and from 29 controls were analyzed. The HRV metrics αS, RMSL, LF, and nLF were significantly lower in infants with CHD than in the controls. Due to the effect of normalization, nHF was higher in CHD infants (P < 0.0001), although absolute HF was lower (P = 0.0461). After adjusting for medications, αS and nLF remained lower and nHF higher in newborns with CHD (P < 0.0005). Conclusions: Infants with complex CHD have depressed autonomic balance in the early postnatal period, which may complicate the fetal–neonatal transition.
Keywords: hypertensive agent; neuromuscular blocking agent; prostaglandin E1; sedative agent; Apgar score; article; artificial ventilation; case control study; controlled study; coronary care unit; electrocardiogram; gestational age; great vessels transposition; head circumference; heart cycle; heart rate variability; human; hypoplastic left heart syndrome; infant; major clinical study; newborn; perinatal period; preoperative period; prospective study; QRS complex; sympathetic tone

Abnormal Left-Hemispheric Sulcal Patterns Correlate with Neurodevelopmental Outcomes in Subjects with Single Ventricular Congenital Heart Disease - Morton, S.U.; Maleyeff, L.; Wypij, D.; Yun, H.J.; Newburger, J.W.; Bellinger, D.C.; Roberts, A.E.; Rivkin, M.J.; Seidman, J.G.; Seidman, C.E.; Grant, P.E.; Im, K. (Cerebral Cortex, 2020)
Neurodevelopmental abnormalities are the most common noncardiac complications in patients with congenital heart disease (CHD). Prenatal brain abnormalities may be due to reduced oxygenation, genetic factors, or less commonly, teratogens. Understanding the contribution of these factors is essential to improve outcomes. Because primary sulcal patterns are prenatally determined and under strong genetic control, we hypothesized that they are influenced by genetic variants in CHD. In this study, we reveal significant alterations in sulcal patterns among subjects with single ventricle CHD (n = 115, 14.7 ± 2.9 years [mean ± standard deviation]) compared with controls (n = 45, 15.5 ± 2.4 years) using a graph-based pattern-analysis technique. Among patients with CHD, the left hemisphere demonstrated decreased sulcal pattern similarity to controls in the left temporal and parietal lobes, as well as the bilateral frontal lobes. Temporal and parietal lobes demonstrated an abnormally asymmetric left-right pattern of sulcal basin area in CHD subjects. Sulcal pattern similarity to control was positively correlated with working memory, processing speed, and executive function. Exome analysis identified damaging de novo variants only in CHD subjects with more atypical sulcal patterns. Together, these findings suggest that sulcal pattern analysis may be useful in characterizing genetically influenced, atypical early brain development and neurodevelopmental risk in subjects with CHD.
Keywords: adolescent; adult; article; brain development; child; cohort analysis; congenital heart disease; controlled study; executive function; exome; female; frontal lobe; genetic variability; heart single ventricle; human; major clinical study; male; mental disease; nuclear magnetic resonance imaging; parietal lobe; priority journal; processing speed; risk factor; whole exome sequencing; working memory

Global, regional, and national burden of congenital heart disease, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017 - Zimmerman, M.S.; Smith, A.G.C.; Sable, C.A.; Echko, M.M.; Wilner, L.B.; Olsen, H.E.; Atalay, H.T.; Awasthi, A.; Bhutta, Z.A.; Boucher, J.L.; Castro, F.; Cortesi, P.A.; et al. (The Lancet Child and Adolescent Health, 2020)
Background: Previous congenital heart disease estimates came from few data sources, were geographically narrow, and did not evaluate congenital heart disease throughout the life course. Completed as part of the Global Burden of Diseases, Injuries, and Risk Factors Study 2017, this study aimed to provide comprehensive estimates of congenital heart disease mortality, prevalence, and disability by age for 195 countries and territories from 1990 to 2017. Methods: Mortality estimates were generated for aggregate congenital heart disease and non-fatal estimates for five subcategories (single ventricle and single ventricle pathway congenital heart anomalies; severe congenital heart anomalies excluding single ventricle heart defects; critical malformations of great vessels, congenital valvular heart disease, and patent ductus arteriosus; ventricular septal defect and atrial septal defect; and other congenital heart anomalies), for 1990 through to 2017. All available global data were systematically analysed to generate congenital heart disease mortality estimates (using Cause of Death Ensemble modelling) and prevalence estimates (DisMod-MR 2·1). Systematic literature reviews of all types of congenital anomalies to capture information on prevalence, associated mortality, and long-term health outcomes on congenital heart disease informed subsequent disability estimates. Findings: Congenital heart disease caused 261 247 deaths (95% uncertainty interval 216 567–308 159) globally in 2017, a 34·5% decline from 1990, with 180 624 deaths (146 825–214 178) being among infants (aged <1 years). Congenital heart disease mortality rates declined with increasing Socio-demographic Index (SDI); most deaths occurred in countries in the low and low-middle SDI quintiles. The prevalence rates of congenital heart disease at birth changed little temporally or by SDI, resulting in 11 998 283 (10 958 658–13 123 888) people living with congenital heart disease globally, an 18·7% increase from 1990 to 2017, and causing a total of 589 479 (287 200–973 359) years lived with disability. Interpretation: Congenital heart disease is a large, rapidly emerging global problem in child health. Without the ability to substantially alter the prevalence of congenital heart disease, interventions and resources must be used to improve survival and quality of life. Our findings highlight the large global inequities in congenital heart disease and can serve as a starting point for policy changes to improve screening, treatment, and data collection. Funding: Bill & Melinda Gates Foundation.
Keywords: article; brain disease; cardiovascular mortality; congenital heart disease; disability; geography; global disease burden; great vessels transposition; heart atrium septum defect; heart single ventricle; heart ventricle septum defect; human; infant mortality; lower respiratory tract infection; mortality rate; patent ductus arteriosus; premature labor; prevalence; rheumatic heart disease; socio demographic index; sudden infant death syndrome; systematic review

Assessment of antiplatelet therapy response in pediatric patients following cardiac surgery by microfluidic assay - Kapileshwarkar, Y.; Gelmini, L.; Tseng, Y.-S.; Jackson, T.; Gao, X.; Richards, K.; Dokas, M.; Walters, H.; Hines, P.C. (Progress in Pediatric Cardiology, 2020)
Introduction: Anti-platelet therapies, like aspirin, are routinely used following many surgical repairs for congenital heart disease to prevent life-threatening thrombotic complications. Optimal dosing is not well studied and determination of real-time dose response to prophylactic aspirin is not routinely performed due to blood volume requirements and poor predictive value of existing platelet function assays (PFAs). Our objective was to study platelet function and thrombosis in post-operative cardiac patients under physiologic shear conditions using a novel collagen-coated microfluidic thrombosis assay (MTA) compared to a standard whole blood aggregometry (WBA) assay before and after clinically and experimentally administered aspirin therapy. Methods: We recruited congenital heart surgical patients with post-operative indications for aspirin therapy at the Children's Hospital of Michigan. Samples of 1.8 mL blood were drawn within 24 h of initiating aspirin (D0) and 24 to 48 h after initiating aspirin (D1). Blood samples were split for use in the MTA and the WBA. The MTA sample was run through collagen coated microfluidic channels at shear stress of 10 dyne/cm2 and pulse frequency of 1.67 Hz to simulate physiologic flow conditions. Each sample was run under untreated conditions (reflects the study subject's endogenous platelet function, D0, D1) and following exogenous aspirin administration (reflects maximum theoretical platelet response to aspirin, +eASA). The kinetics of thrombus formation was assessed as area percent of signal intensity (total fluorescent intensity, TFI) of thrombosis at 6 &10 min and as area under curve (AUC) for MTA and as AUC and impedance at 6 min for WBA. Results: Results from MTA and WBA on pre- and post-aspirin blood samples collected from 18 subjects, with and without exogenously added aspirin, were analyzed in this study. Fold changes for AUC were calculated for each test and were compared using Wilcoxon signed rank test; this showed no statistically significant difference. Three of the patients were found to have no response to endogenous or exogenous aspirin. Conclusions: We observed that measured platelet function is variable and potential sources of variability could be sample source, timing of sample from bypass, platelet count, transfusions and others. Standard aspirin doses might not be adequate for patients who are at high risk of thrombosis. In this study, we demonstrate the feasibility of employing microfluidic thrombosis assay to assess real time clinical platelet function in the cardiac ICU setting. Microfluidic assays provide real time assessment of platelet function under physiologic flow conditions and might be helpful with optimizing aspirin doses. Further studies on larger cohorts are required to validate this possibility.
Keywords: acetylsalicylic acid; collagen; ketorolac; adolescent; anticoagulant therapy; aortic stenosis; article; blood aggregometry assay; blood clotting; blood examination; blood sampling; cardiac patient; child; clinical article; controlled study; coronary care unit; drug indication; Fallot tetralogy; female; heart single ventricle; heart surgery; human; in vitro study; infant; male; microfluidic analysis; newborn; pediatric patient; platelet count; postoperative thrombosis; priority journal; prospective study; pulse rate; shear rate; shear stress; thrombocyte activation; thrombocyte function; treatment response

Association of Maternal Psychological Distress with in Utero Brain Development in Fetuses with Congenital Heart Disease - Wu, Y.; Kapse, K.; Jacobs, M.; Niforatos-Andescavage, N.; Donofrio, M.T.; Krishnan, A.; Vezina, G.; Wessel, D.; Du Plessis, A.; Limperopoulos, C. (JAMA Pediatrics, 2020)
Importance: Prenatal maternal psychological distress can result in detrimental mother and child outcomes. Maternal stress increases with receipt of a prenatal diagnosis of fetal congenital heart disease (CHD); however, the association between maternal stress and the developing brain in fetuses with CHD is unknown. Objective: To determine the association of maternal psychological distress with brain development in fetuses with CHD. Design, Setting, and Participants: This longitudinal, prospective, case-control study consecutively recruited 48 pregnant women carrying fetuses with CHD and 92 healthy volunteers with low-risk pregnancies from the Children's National Health System between January 2016 and September 2018. Data were analyzed between January 2016 and June 2019. Exposures: Fetal CHD and maternal stress, anxiety, and depression. Main Outcomes and Measures: Maternal stress, anxiety, and depression were measured using the Perceived Stress Scale, Spielberger State-Trait Anxiety Inventory, and Edinburgh Postnatal Depression Scale, respectively. Volumes of fetal total brain, cerebrum, left and right hippocampus, cerebellum, and brainstem were determined from 3-dimensionally reconstructed T2-weighted magnetic resonance imaging (MRI) scans. Results: This study included 223 MRI scans from 140 fetuses (74 MRIs from 48 fetuses with CHD and 149 MRIs from 92 healthy fetuses) between 21 and 40 weeks' gestation. Among 48 women carrying fetuses with CHD, 31 (65%) tested positive for stress, 21 (44%) for anxiety, and 14 (29%) for depression. Among 92 pregnant women carrying healthy fetuses, 25 (27%) tested positive for stress, 24 (26%) for anxiety, and 8 (9%) for depression. Depression scores were higher among 17 women carrying fetuses with single-ventricle CHD vs 31 women carrying fetuses with 2-ventricle CHD (3.8; 95% CI, 0.3 to 7.3). Maternal stress and anxiety were associated with smaller left hippocampal (stress: -0.003 cm3; 95% CI, -0.005 to -0.001 cm3), right hippocampal (stress: -0.004; 95% CI, -0.007 to -0.002; trait anxiety: -0.003; 95% CI, -0.005 to -0.001), and cerebellar (stress: -0.06; 95% CI, -0.09 to -0.02) volumes only among women with fetal CHD. Impaired hippocampal regions were noted in the medial aspect of left hippocampal head and inferior aspect of right hippocampal head and body. Impaired cerebellar regions were noted in the anterior superior aspect of vermal and paravermal regions and the left cerebellar lobe. Conclusions and Relevance: These findings suggested that psychological distress among women carrying fetuses with CHD is prevalent and is associated with impaired fetal cerebellar and hippocampal development. These data underscore the importance of universal screening for maternal psychological distress, integrated prenatal mental health support, and targeted early cognitive-behavioral interventions given that stress is a potentially modifiable risk factor in this high-risk population..
Keywords: adult; anxiety disorder; article; brain development; brain size; brain stem; case control study; cerebellum; congenital heart disease; controlled study; depression; distress syndrome; Edinburgh Postnatal Depression Scale; female; fetus; heart single ventricle; hippocampus; human; image reconstruction; in utero brain development; longitudinal study; maternal stress; neuroimaging; nuclear magnetic resonance imaging; outcome assessment; Perceived Stress Scale; pregnant woman; priority journal; prospective study; right hippocampus; State Trait Anxiety Inventory

Survival, Neurocognitive, and Functional Outcomes After Completion of Staged Surgical Palliation in a Cohort of Patients With Hypoplastic Left Heart Syndrome - Atallah, J.; Garcia Guerra, G.; Joffe, A.R.; Bond, G.Y.; Islam, S.; Ricci, M.F.; AlAklabi, M.; Rebeyka, I.M.; Robertson, C.M.T. (Journal of the American Heart Association, 2020)
Background: Management of patients with hypoplastic left heart syndrome has benefited from advancements in medical and surgical care. Outcomes have improved, although survival and long-term functional and cognitive deficits remain a concern. Methods and Results: This is a cohort study of all consecutive patients with hypoplastic left heart syndrome undergoing surgical palliation at a single center. We aimed to examine demographic and perioperative factors from each surgical stage for their association with survival and neurocognitive outcomes. A total of 117 consecutive patients from 1996 to 2010 underwent surgical palliation. Seventy patients (60%) survived to the Fontan stage and 68 patients (58%) survived to undergo neurocognitive assessment at a mean (SD) age of 56.6 months (6.4 months). Full-scale, performance, and verbal intelligence quotient, as well as visual-motor integration mean (SD) scores were 86.7 (16.1), 86.3 (15.8), 88.8 (17.2), and 83.2 (14.8), respectively. On multivariable analysis, older age at Fontan, sepsis peri-Norwood, lowest arterial partial pressure of oxygen postbidirectional cavopulmonary anastomosis, and presence of neuromotor disability pre-Fontan were strongly associated with lower scores for all intelligence quotient domains. Older age at Fontan and sepsis peri-Norwood remained associated with lower scores for all intelligence quotient domains in a subgroup analysis excluding patients with disability pre-Fontan or with chromosomal abnormalities. Conclusions: Older age at Fontan and sepsis are among independent predictors of poor neurocognitive outcomes for patients with hypoplastic left heart syndrome. Further studies are required to identify the appropriate age range for Fontan completion, balancing a lower risk of acute and long-term hemodynamic complications while optimizing long-term neurocognitive outcomes.
Keywords: age; arterial pressure; article; Blalock Taussig shunt; cavopulmonary connection; child; clinical outcome; cognition; cognition assessment; cohort analysis; epilepsy; extracorporeal oxygenation; female; follow up; Fontan procedure; full scale intelligence quotient score; functional behavior; human; hypoplastic left heart syndrome; intelligence quotient; long term survival; major clinical study; male; mental performance; mortality rate; motor dysfunction; neurologic examination; Norwood procedure; outcome assessment; overall survival; palliative therapy; perception deafness; performance intelligence quotient score; perioperative period; predictive value; preschool child; priority journal; risk factor; sepsis; survival rate; treatment outcome; verbal intelligence quotient score; visual impairment; visuomotor coordination

Evidence of Systemic Absorption of Enteral Budesonide in Patients with Fontan-Associated Protein-Losing Enteropathy - Roberts, R.O.; Di Maria, M.V.; Brigham, D.; Hsu, S. (Pediatric Cardiology, 2020)
To evaluate for evidence of systemic glucocorticoid absorption in cases of Fontan-associated protein-losing enteropathy (PLE) treated with enteral budesonide, we reviewed the charts of 27 patients with Fontan-associated PLE followed at Children’s Hospital Colorado from 2005 to 2018. Cases were excluded for lack of budesonide thserapy or a treatment duration of less than 6 months. Charts were examined by two endocrinologists for review of prior biochemical endocrine evaluations, alterations in linear growth, and physical exam findings consistent with steroid excess. Twelve patients met inclusion criteria. Eight had prior documented cortisol screening. Three patients were tested while on treatment with a median fasting AM cortisol of 0.9 mcg/dL; two of these had a concomitantly measured ACTH, both below the detectable limit. Five patients were tested while weaning or having discontinued budesonide, with a median fasting AM cortisol of 9.1 mcg/dL. Eleven patients had decreases in height velocity associated with starting budesonide. Six patients had documentation of cushingoid features by an endocrinologist. In this cohort of children treated with budesonide for PLE following Fontan, clinical signs of systemic glucocorticoid absorption were frequent. Cortisol secretion was suppressed while on therapy, with adrenal recovery noted once budesonide was discontinued. Growth failure and cushingoid features were common findings. While these findings should be confirmed in larger cohorts, we recommend that the evaluation for systemic absorption of exogenous steroids be considered in patients treated with long-term enteral budesonide given the potential risk for adrenal crisis in times of physiologic stressors.
Keywords: budesonide; corticosteroid; corticotropin derivative; corticotropin releasing factor; glucocorticoid; hydrocortisone; prednisolone; spironolactone; adrenal cortex insufficiency; adrenal suppression; article; child; clinical article; cohort analysis; controlled study; Cushingoid syndrome; drug absorption; drug metabolism; endocrinologist; female; growth disorder; human; incidence; male; physical examination; pleiotropy; protein losing gastroenteropathy; quality of life; retrospective study; screening test; treatment duration

Dobutamine stress testing in patients with Fontan circulation augmented by biomechanical modeling - Ruijsink, B.; Zugaj, K.; Wong, J.; Pushparajah, K.; Hussain, T.; Moireau, P.; Razavi, R.; Chapelle, D.; Chabiniok, R. (PLoS ONE, 2020)
Understanding (patho)physiological phenomena and mechanisms of failure in patients with Fontan circulation—a surgically established circulation for patients born with a functionally single ventricle—remains challenging due to the complex hemodynamics and high inter-patient variations in anatomy and function. In this work, we present a biomechanical model of the heart and circulation to augment the diagnostic evaluation of Fontan patients with early-stage heart failure. The proposed framework employs a reduced-order model of heart coupled with a simplified circulation including venous return, creating a closed-loop system. We deploy this framework to augment the information from data obtained during combined cardiac catheterization and magnetic resonance exams (XMR), performed at rest and during dobutamine stress in 9 children with Fontan circulation and 2 biventricular controls. We demonstrate that our modeling framework enables patient-specific investigation of myocardial stiffness, contractility at rest, contractile reserve during stress and changes in vascular resistance. Hereby, the model allows to identify key factors underlying the pathophysiological response to stress in these patients. In addition, the rapid personalization of the model to patient data and fast simulation of cardiac cycles make our framework directly applicable in a clinical workflow. We conclude that the proposed modeling framework is a valuable addition to the current clinical diagnostic XMR exam that helps to explain patient-specific stress hemodynamics and can identify potential mechanisms of failure in patients with Fontan circulation.
Keywords: dobutamine; adolescent; article; biomechanics; cardiac muscle; child; clinical article; conceptual framework; controlled study; disease classification; exercise test; Fontan procedure; heart catheterization; heart cycle; heart failure; heart muscle contractility; human; muscle rigidity; nuclear magnetic resonance imaging; pathophysiology; preschool child; school child; vascular resistance; venous return; workflow

Growth, development, and quality of life in children with congenital heart disease - Maya, S.; Gunawijaya, E.; Yantie, N.P.V.K.; Windiani, I.G.A.T. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Despite the advances in medical and surgical care have improved the survival rates of children with congenital heart disease (CHD), they still remain risky for nutritional, cognitive problems, and quality of life. Those impacts vary according to the severity of heart lesions and still manifested years after surgery. AIM: The objective of this study was to compare growth, development, and quality of life between cyanotic and acyanotic CHD. METHODS: The study was performed on 52 patients aged 24–69 months old from June to January 2018 in Sanglah Pediatric Cardiology clinic used WHO Anthro software, The Mullen Scales of Early Learning and PedsQL Cardiac module. RESULTS: We found significant different proportion of underweight 11.5% in acyanotic children, 42.3% in cyanotic by weight/age z-score <−2SD (p = 0.033). Height/ age z-score <−3SD 38.5% in cyanotic versus 11.5% in acyanotic (p = 0.025). The cyanotic showed a significant difference in cognitive function, presented by early learning composite score (p = 0.044) particularly in gross motor (p = 0.034) and receptive language (0.047). Quality of life differs significantly between both groups in heart problem and therapy (p = 0.042), treatment anxiety (p = 0.016), cognitive problems (p = 0.038), and communication (p = 0.022). CONCLUSION: Development, growth problems, and lower quality of life are common in cyanotic children, thus highlight the need for longitudinal surveillance.
Keywords: oxyhemoglobin; acyanotic heart disease; anthropometry; anxiety; article; atrioventricular septal defect; child; cognition; cognitive defect; communication skill; congenital heart disease; cross-sectional study; cyanotic heart disease; development; echocardiography; female; growth; heart catheterization; heart injury; heart surgery; human; infant; language disability; lung vascular resistance; major clinical study; male; malnutrition; mental deficiency; motor function test; nutritional assessment; oxygen saturation; Pediatric Quality of Life Inventory; physical appearance; pulmonary valve atresia; quality of life; questionnaire; tricuspid valve atresia; underweight

Birth defects in Taiwan: A 10-year nationwide population-based, cohort study - Chen, L.-J.; Chiou, J.-Y.; Huang, J.-Y.; Su, P.-H.; Chen, J.-Y. (Journal of the Formosan Medical Association, 2020)
Background/Purpose: Birth defects (BDs) are main causes of mortality and disability in infants and children. The aims of this study were to analyze the prevalence, types and risk factors of BDs in Taiwan. Methods: Data of all births (including live and stillbirths), types, characteristics, and associated risk factors of BDs were obtained from the National Birth Registry and National Health Insurance Research Data base in Taiwan between 2005 and 2014. Birth defects were coded according to International Classification of Diseases 9th Revision-Clinical Modification codes 740–759. Results: A total of 55,299 infants were diagnosed as having BDs among 2,033,004 births. The prevalence of BDs was 271.66 per 10,000 births. The prevalence of BDs did not change significantly between 2005 and 2014, there was a higher birth rate and lower BDs in 2012 (year of dragon) in Taiwan. The most common type of BDs was cardiovascular abnormalities, and ventricular septal defect was the most common disease. Extreme maternal age (<18 years or ≧30 years), preterm, and low birth weight were associated with BDs. Maternal diseases associated with BDs included hypertension, cardiovascular diseases, renal diseases, genitourinary infections, anemia, mental disorders, and diabetes mellitus. Conclusion: The prevalence of BDs was 271.66 per 10,000 births. The most common types of BDs were cardiovascular abnormalities. If we can reduce maternal chronic diseases, we will decrease the prevalence of BDs.
Keywords: achondroplasia; anemia; anencephalus; anophthalmia; anus atresia; aortic arch interruption; aortic coarctation; aortic valve stenosis; article; atrioventricular septal defect; attributable risk; bile duct atresia; birth weight; bladder exstrophy; cardiovascular disease; cardiovascular malformation; choana atresia; chromosome aberration; chronic disease; cleft lip with or without cleft palate; cleft palate; clubfoot; cohort analysis; common bile duct cyst; congenital cataract; congenital diaphragm hernia; congenital heart disease; congenital hip dislocation; congenital hydrocephalus; congenital malformation; congenital skin disease; cryptorchism; cystic adenomatoid malformation; encephalocele; epispadias; esophagus atresia; Fallot tetralogy; female; gastroschisis; gestational age; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; hermaphroditism; Hirschsprung disease; holoprosencephaly; human; hydronephrosis; hypoplastic left heart syndrome; hypospadias; ICD-9-CM; intestine atresia; karyotype 47,XXY; kidney agenesis; kidney disease; kidney polycystic disease; laryngomalacia; limb defect; live birth; low birth weight; lung agenesis; lung sequestration; lung vein drainage anomaly; major clinical study; male; maternal age; maternal diabetes mellitus; maternal disease; maternal hypertension; meningomyelocele; mental disease; microcephaly; microphthalmia; multicystic dysplastic kidney; newborn; omphalocele; patent ductus arteriosus; polydactyly; population research; prematurity; prevalence; pulmonary valve atresia; pulmonary valve stenosis; pylorus stenosis; risk factor; spinal dysraphism; stillbirth; syndactyly; Taiwan; tracheoesophageal fistula; tracheomalacia; tricuspid valve atresia; tricuspid valve stenosis; trisomy 13; trisomy 18; trisomy 21; Turner syndrome; urinary tract obstruction

Early Integration of Palliative Care in Families of Children with Single Ventricle Congenital Heart Defects: A Quality Improvement Project to Enhance Family Support - Davis, J.A.M.; Bass, A.; Humphrey, L.; Texter, K.; Garee, A. (Pediatric Cardiology, 2020)
Children with single ventricle congenital heart defects (SVCHD) experience a significant risk of early mortality throughout their lifespan, particularly during their first year of life. Due to the intense care needed for these children and families, pediatric palliative care (PPC) team consults should be routine; however, medical staff are often reluctant to broach the idea of PPC to families. The involvement of PPC for many carries with it an association to end-of-life (EOL) care. Setting the standard of PPC involvement from the time of admission for the first palliative surgery led to increased family support, decreased days to consult, improved acceptance and communication. The purpose of this article is to describe a quality improvement project of early integration of PPC with families of children with SVCHD. Lessons learned will be presented, including the resources needed and the barriers encountered in assimilating PPC into the standard of care for all patients with SVCHD. The single ventricle (SV) and PPC teams collaborated to enhance the support given to SV families. Education was initiated with cardiology and PPC providers to understand the goal of consistent PPC consults beginning after birth for patients with SVCHD. Parents were educated during fetal consultation regarding the involvement of the PPC team. The SV team ensured compliance with the PPC initiative by identifying eligible patients and requesting consult orders from the primary providers. PPC consultation increased significantly over the 40 month study period to nearly 100% compliance for children with SVCHD who are undergoing pre-Fontan surgery. In addition, mean days to consult decreased dramatically during the study to a current average of 3 days into the patient’s hospitalization; the data likely suggest that more PPC consults were routinely ordered versus urgently placed for unexpected complications. Data indicate that patients are being followed by the PPC team at an earlier age and stage in their SV journey which allows for more opportunity to provide meaningful support to these patients and families. The early involvement of the PPC team for children with SV physiology was operationally feasible and was accepted by families, thus allowing PPC providers to establish a therapeutic relationship early in the disease trajectory with the family. It allowed more continuity throughout the SV journey in a proactive fashion rather than a reactive manner.
Keywords: age; article; child; collaborative care team; congenital heart malformation; disease classification; family service; fetus monitoring; Fontan procedure; health care quality; heart single ventricle; hospitalization; human; major clinical study; medical information; palliative therapy; patient care; patient compliance; social support; standardization; terminal care

Management of People With a Fontan Circulation: a Cardiac Society of Australia and New Zealand Position statement - Zentner, D.; Celermajer, D.S.; Gentles, T.; d'Udekem, Y.; Ayer, J.; Blue, G.M.; Bridgman, C.; Burchill, L.; Cheung, M.; Cordina, R.; Culnane, E.; Davis, A.; et al. (Heart Lung and Circulation, 2020)
The Fontan circulation describes the circulatory state resulting from an operation in congenital heart disease where systemic venous return is directed to the lungs without an intervening active pumping chamber. As survival increases, so too does recognition of the potential health challenges. This document aims to allow clinicians, people with a Fontan circulation, and their families to benefit from consensus agreement about management of the person with a Fontan circulation. The document was crafted with input from a multidisciplinary group of health care providers as well as individuals with a Fontan circulation and families. It is hoped that the shared common vision of long-term wellbeing will continue to drive improvements in care and quality of life in this patient population and eventually translate into improved survival. Keypoints: • Lifelong quality medical care with access to multidisciplinary services, is of prime importance. Care includes regular tests for surveillance of health status. • Transition from paediatric to adult care is an active process that should commence during early adolescence and continue until successful engagement with adult congenital cardiology care. • Children and adults with a Fontan circulation often have reduced peak exercise capacity (on average, 60–65% of predicted values). Increasingly, evidence suggests exercise training may improve exercise capacity and cardiovascular function. • People with a Fontan circulation have higher rates of anxiety and behavioural disorders, and there needs to be a low threshold for the provision of mental health care. • Pregnancy has increased maternal and fetal risks, and pre-conception multidisciplinary assessment and counselling is essential. • Atrial arrhythmias are common, often late after Fontan surgical repair and due to intra-atrial re-entry or “flutter” mediated by atrial stretch and scarring. Some anti-arrhythmic agents, most classically the type IC drugs, may allow haemodynamically unstable, life-threatening 1:1 AV conduction. • Anticoagulation with warfarin is routine care in patients with atrial arrhythmias. • In patients with recurrent atrial arrhythmias, catheter ablation or surgical conversion may be considered. • The Fontan circulation is an ideal substrate for thrombus formation and may result in intracardiac or intravascular thrombosis, ischaemic stroke, or other embolic phenomena. Antiplatelet and anticoagulant agents are commonly prescribed for thromboprophylaxis in patients with a Fontan circulation. Evidence suggests that treatment with one of these agents is advantageous, but there is no consensus on which is optimal. Despite treatment, symptomatic thromboembolic events are associated with significant mortality. • Heart failure is the leading cause of morbidity and mortality. Diuretics provide symptomatic relief, however standard heart failure medical therapy is not of proven benefit. • Though not well understood, there is increasing concern regarding progressive liver disease with a long-term risk of hepatocellular carcinoma. • Despite early higher mortality post heart transplant, these individuals have better long-term survival outcomes compared with many other heart transplant recipients.
Keywords: arterial stent; artificial heart; biventricular assist device; implantable cardioverter defibrillator; right ventricular assist device; ventricular assist device; angiotensin receptor antagonist; beta adrenergic receptor blocking agent; dipeptidyl carboxypeptidase inhibitor; diuretic agent; endothelin receptor antagonist; phosphodiesterase V inhibitor; spironolactone; vasodilator agent; warfarin; adolescence; antibiotic prophylaxis; anticoagulation; Australia; blood clotting; bronchitis; cardiovascular function; cardiovascular magnetic resonance; cardiovascular mortality; catheter ablation; clinical practice; congenital heart disease; contraception; echocardiography; electrocardiography; exercise; exercise test; fertility; Fontan procedure; gastroscopy; genetic disorder; genetic screening; health care access; health status; heart atrium arrhythmia; heart catheterization; heart failure; heart pacing; heart single ventricle; heart transplantation; heart valve regurgitation; heart ventricle arrhythmia; human; incidence; intracardiac thrombosis; kidney dysfunction; leisure; letter; liver cell carcinoma; liver disease; lung vascular resistance; medical society; mental health care; morbidity; New Zealand; palliative therapy; patient care; patient counseling; patient monitoring; patient referral; patient safety; plastic bronchitis; pregnancy; prescription; priority journal; protein losing gastroenteropathy; pulmonary hypertension; quality of life; sudden cardiac death; surgical technique; survival rate; systemic vascular resistance; thromboembolism; time to treatment; transitional care; treatment contraindication; treatment indication; wellbeing

Altered frontal white matter microstructure is associated with working memory impairments in adolescents with congenital heart disease: A diffusion tensor imaging study - Ehrler, M.; Latal, B.; Kretschmar, O.; von Rhein, M.; O'Gorman Tuura, R. (NeuroImage: Clinical, 2020)
Children and adolescents with congenital heart disease (CHD) are at risk for mild to moderate cognitive impairments. In particular, impaired working memory performance has been found in CHD patients of all ages. Working memory is an important domain of higher order cognitive function and is crucial for everyday activities, with emerging importance in adolescence. However, the underlying neural correlate of working memory impairments in CHD is not yet fully understood. Diffusion tensor imaging and tract based spatial statistics analyses were conducted in 47 adolescent survivors of childhood cardiopulmonary bypass surgery (24 females) and in 44 healthy controls (24 females) between 11 and 16 years of age (mean age = 13.9, SD = 1.6). Fractional anisotropy (FA) of white matter diffusion was compared between groups and was correlated with working memory performance, derived from the Wechsler Intelligence Scale for Children-IV. CHD patients had significantly poorer working memory compared to controls (p = 0.001). Widespread bilateral reduction in FA was observed in CHD patients compared to healthy controls (threshold-free cluster enhancement (TFCE) corrected p < 0.05). This reduction in FA was present both in cyanotic and acyanotic CHD patients compared to healthy controls (both p < 0.001). The FA reduction in the frontal lobe, mainly in the forceps minor, was associated with poorer working memory performance in both patients with CHD and healthy controls (TFCE corrected p < 0.05). The current findings underline that in CHD patients, irrespective of disease severity, disrupted or delayed maturation of white matter may persist into adolescence and is associated with working memory impairments, particularly if present in the frontal lobe. Adolescence, which is a crucial period for prefrontal brain maturation, may offer a window of opportunity for intervention in order to support the maturation of frontal brain regions and therefore improve higher order cognitive function in patients with CHD.
Keywords: adolescent; aortic coarctation; aortic stenosis; article; brain fornix; capsula interna; cardiopulmonary bypass; cerebral peduncle; child; cingulum (brain); clinical article; congenital heart disease; controlled study; corona radiata (brain); corpus callosum; cyanotic heart disease; diffusion tensor imaging; double inlet left ventricle; external capsule; Fallot tetralogy; female; fractional anisotropy; frontal lobe; genu (corpus callosum); great vessels transposition; heart atrium septum defect; heart ventricle septum defect; human; image processing; inferior longitudinal fasciculus; intelligence quotient; left hemisphere; lung vein drainage anomaly; male; memory disorder; neuroanatomy; neuroimaging; occipitofrontal fasciculus; outcome assessment; priority journal; pulmonary valve atresia; pulmonary valve stenosis; pyramidal tract; right hemisphere; splenium; superior longitudinal fasciculus; thalamus; tricuspid valve atresia; uncinate fasciculus; Wechsler intelligence scale for children; white matter; working memory

Awareness assessment for parents of children with congenital heart diseases regarding fetal echocardiography - Rakha, S. (Turkish Journal of Pediatrics, 2020)
Background and objectives. The high recurrence rate of congenital heart disease (CHD) in siblings was the rationale for recommending fetal echocardiography. However, in a developing country like Egypt, there are limited fetal echocardiographic examinations under this category. The study was conducted to assess knowledge about fetal echocardiography amongst parents of children with CHD. Method. A questionnaire survey was conducted in a tertiary pediatric hospital from June to December 2018. The study included parents having children with CHD follow up in the outpatient clinic or admitted in the pediatric cardiology ward. The questionnaire included demographic data of parents regarding sex, age, education, and residence. It also includes a detailed inquiry about parents’ knowledge regarding the availability, safety, and value of fetal echocardiography. Results. Participants were 200 parents, mostly mothers 159 (79.5%). The median age of parents included in the study was 33.5 (29-40) years. Regarding awareness, 134 (67%) did not know any prenatal diagnostic investigation for CHD, 46 (23%) knew fetal echocardiography, and 20 (10%) named other tools. Nevertheless, 34% of parents thought they would need fetal echocardiography in a subsequent pregnancy. Although 178 (89%) of parents thought it might be a safe investigation, 33% did not think it will have additional benefits over postnatal echocardiography. The age of the patient and age of the participating parent were the only statistically significant predictors for parents knowledge on fetal echocardiography existence with p= 0.008, 95% CI=1.0391.282 and p= 0.015, 95% CI = 0.864-0.984, respectively. Conclusion. Parents of children with CHD have significant knowledge gaps regarding Fetal Echocardiography. Our findings suggest that the current parent counseling is inadequate and needs further focus, especially in developing countries, to promote parents’ understanding of the prenatal cardiac diagnosis. Data on fetal echocardiography should be clarified at the initial diagnosis of pediatric CHD.
Keywords: adult; article; child; cohort analysis; congenital heart disease; cyanotic heart disease; Down syndrome; echocardiography; education; female; follow up; heart arrhythmia; heart atrium septum defect; heart injury; hospitalization; human; hypoplastic left heart syndrome; infant; LEOPARD syndrome; major clinical study; male; Noonan syndrome; parental attitude; postnatal care; pregnancy; pregnancy diabetes mellitus; questionnaire; recurrence risk

Evaluation of a ten-year team-based collaborative capacity-building program for pediatric cardiac surgery in uzbekistan: Lessons and implications - Han, S.; Choi, S.; Heo, J.; Park, J.; Kim, W.-H. (Annals of Global Health, 2020)
Background: Most children who have congenital heart disease in low-and middle-income countries (LMICs), including Uzbekistan, do not receive adequate and timely pediatric cardiac surgical care. To strengthen the surgical capacity of a local pediatric cardiac surgery team in Tashkent, Uzbekistan, the JW LEE Center for Global Medicine at Seoul National University College of Medicine has developed a team-based training program and has been collaboratively conducting surgeries and care in order to transfer on-site knowledge and skills from 2009 to 2019. Objectives: To evaluate the long-term effects of the collaborative program on the cardiac surgical capacity of medical staff (teamwork, surgical complexity, and patients’ pre-surgical weights) as well as changes in the lives of the patients and their families. To derive lessons and challenges for other pediatric cardiac surgical programs in LMICs. Methods: To assess the effects of this ten-year long program, a mixed-methods design was developed to examine the trend of surgical complexity measured by Risk Adjustment for Congenital Heart Surgery 1 score (RACHS-1) and patients’ pre-surgical weights via medical record review (surgical cases: n = 107) during the decade. Qualitative data was analyzed from in-depth interviews (n = 31) with Uzbek and Korean medical staff (n = 10; n = 4) and caregivers (n = 17). Findings: During the decade, the average RACHS-1 of the cases increased from 1.9 in 2010 to 2.78 in 2019. The average weight of patients decreased by 2.8 kg from 13 kg to 10.2 kg during the decade. Qualitative findings show that the surgical capacity, as well as attitudes toward patients and colleagues of the Uzbek medical staff, improved through the effective collaboration between the Uzbek and Korean teams. Changes in the lives of patients and their families were also found following successful surgery. Conclusions: Team-based training of the workforce in Uzbekistan was effective in improving the surgical skills, teamwork, and attitudes of medical staff, in addition, a positive impact on the life of patients and their families was demonstrated. It can be an effective solution to facilitate improvements in pediatric cardiovascular disease in LMICs if training is sustained over a long period.
Keywords: administrative personnel; anesthesiologist; aortic coarctation; article; atrioventricular septal defect; capacity building; cardiac surgeon; cardiologist; caregiver; child; collaborative care team; congenital heart disease; Ebstein anomaly; Fallot tetralogy; family; female; great vessels transposition; health personnel attitude; health program; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; heart surgery; heart ventricle septum defect; human; low income country; lung vein drainage anomaly; major clinical study; male; medical record review; medical staff; middle income country; nurse; operating room personnel; pediatric surgery; perfusionist; preschool child; professional competence; program evaluation; pulmonary valve atresia; qualitative research; quantitative study; risk assessment; scientist; teamwork; tricuspid valve atresia; Uzbekistan

Maternal occupational exposure and congenital heart defects in offspring - Spinder, N.; Bergman, J.E.H.; Kromhout, H.; Vermeulen, R.; Corsten-Janssen, N.; Boezen, H.M.; du Marchie Sarvaas, G.J.; de Walle, H.E.K. (Scandinavian Journal of Work, Environment and Health, 2020)
Objectives Congenital heart defects (CHD) are the most prevalent congenital anomalies. This study aims to examine the association between maternal occupational exposures to organic and mineral dust, solvents, pesti-cides, and metal dust and fumes and CHD in the offspring, assessing several subgroups of CHD. Methods For this case–control study, we examined 1174 cases with CHD from EUROCAT Northern Netherlands and 5602 controls without congenital anomalies from the Lifelines cohort study. Information on maternal jobs held early in pregnancy was collected via self-administered questionnaires, and job titles were linked to occupational exposures using a job exposure matrix. Results An association was found between organic dust exposure and coarctation of aorta [adjusted odds ratio (ORadj) 1.90, 95% confidence interval (CI) 1.01–3.59] and pulmonary (valve) stenosis in combination with ventricular septal defect (ORadj 2.68, 95% CI 1.07–6.73). Mineral dust exposure was associated with increased risk of coarctation of aorta (ORadj 2.94, 95% CI 1.21–7.13) and pulmonary valve stenosis (ORadj 1.99, 95% CI 1.10–3.62). Exposure to metal dust and fumes was infrequent but was associated with CHD in general (ORadj 2.40, 95% CI 1.09–5.30). Exposure to both mineral dust and metal dust and fumes was associated with septal defects (ORadj 3.23, 95% CI 1.14–9.11). Any maternal occupational exposure was associated with a lower risk of aortic stenosis (ORadj 0.32, 95% CI 0.11–0.94). Conclusions Women should take preventive measures or avoid exposure to mineral and organic dust as well as metal dust and fumes early in pregnancy as this could possibly affect foetal heart development.
Keywords: folic acid; pesticide; solvent; adolescent; adult; alcohol consumption; aortic coarctation; aortic stenosis; article; atrioventricular septal defect; bicuspid aortic valve; case control study; cohort analysis; congenital heart malformation; controlled study; dust; Fallot tetralogy; female; fume; heart atrium septum defect; heart left ventricle outflow tract obstruction; heart right ventricle outflow tract obstruction; heart septum defect; heart ventricle septum defect; human; hypoplastic left heart syndrome; infant; major clinical study; male; maternal exposure; maternal smoking; mineral dust; Netherlands; obesity; occupational exposure; organic dust; pregnancy; priority journal; progeny; pulmonary valve atresia; pulmonary valve stenosis; questionnaire; underweight; young adult

Physical exercise training in patients with a Fontan circulation: A systematic review - Scheffers, L.E.; Berg, L.E.M.V.; Ismailova, G.; Dulfer, K.; Takkenberg, J.J.M.; Helbing, W.A. (European Journal of Preventive Cardiology, 2020)
Background: Patients with a Fontan circulation have a reduced exercise capacity, which is an important prognostic predictor of morbidity and mortality. A way to increase exercise capacity in Fontan patients might be exercise training. This systematic review assesses the effects of exercise training investigated in Fontan patients in order to provide an overview of current insights. Design and methods: Studies evaluating an exercise training intervention in Fontan patients published up to February 2020 were included in this systematic review. Results: From 3000 potential studies, 16 studies reported in 22 publications met the inclusion criteria. In total, 264 Fontan patients with mean age range 8.7–31 years, were included. Different training types including inspiratory muscle training, resistance training and aerobic training were investigated. Main outcome measures reported were peak oxygen uptake, cardiac function, lung function, physical activity levels and quality of life. Peak oxygen uptake increased significantly in 56% of the studies after training with an overall mean increase of +1.72 ml/kg/min (+6.3%). None of the studies reported negative outcome measures related to the exercise programme. In four studies an adverse event was reported, most likely unrelated to the training intervention. Conclusions: Exercise training in Fontan patients is most likely safe and has positive effects on exercise capacity, cardiac function and quality of life. Therefore exercise training in Fontan patients should be encouraged. Further studies are required to assess the optimal training type, intensity, duration and long-term effects.
Keywords: adolescent; adult; aerobic capacity; article; child; congenital heart malformation; endurance; female; Fontan procedure; heart function; human; lung function; male; muscle training; outcome assessment; physical activity; quality of life; resistance training; school child; systematic review

Severe right ventricular dysplasia with absent pulmonary valve syndrome and tricuspid atresia: A literature review - Parikh, K.; Muniz, J.C.; Welch, E.; Aldousany, A.; Sasaki, N. (Congenital Heart Disease, 2020)
This is a newborn male prenatally diagnosed with severe right ventricular (RV) hypertrophy and depressed function, aneurysmal dilation of the main pulmonary artery and tachyarrhythmia. Postnatally, he required immediate intuba-tion and inotropic support. Echocardiogram revealed a large dysplastic RV, absent pulmonary valve syndrome (APVS), markedly dilated pulmonary arteries and tri-cuspid atresia (TA). The trabecular portion of the RV was excessively trabeculated and severely dilated. Inflow and infundibular walls were thin, with multiple infun-dibular aneurysms. There was APVS with free regurgitation and massively dilated pulmonary arteries. The RV bulged into the LV, though there was no outflow tract obstruction. The LV had mildly depressed systolic function. Computed tomogra-phy angiography showed marked dilation of the main and branch pulmonary arteries, with compression of the airway. This, along with profound anasarca, pro-hibited weaning of ventilatory support. Ventricular tachycardia contributed to low cardiac output. Genetic testing revealed a heterozygous variant in the desmopla-kin (DSP) gene, which is associated with familial arrhythmogenic RV dysplasia and dilated cardiomyopathy. The parents opted to withdraw care. Severe RV dys-plasia associated with APVS and TA has previously been reported, however the degree of RV dilation with primitive myocardium in this case is profound. Further, presence of both fetal and postnatal ventricular tachycardia contributing to low cardiac is a novel presentation. This demonstrates that the overall poor prognosis was multifactorial.
Keywords: airway; anasarca; aneurysm; angiography; article; assisted ventilation; canine tooth; compression; congestive cardiomyopathy; echocardiography; fetus; forward heart failure; genetic association; genetic screening; genetic susceptibility; heart right ventricle dysplasia; heart right ventricle hypertrophy; heart ventricle tachycardia; heterozygosity; human; inotropism; male; newborn; obstruction; prognosis; pulmonary artery; pulmonary valve; tricuspid valve atresia; weaning

Interventions and neonatal outcomes of fetuses with hypoplastic left heart syndrome and congenital diaphragmatic hernia: a systematic review - Kanade, R.; Shazly, S.; Ruano, R. (Journal of Maternal-Fetal and Neonatal Medicine, 2020)
Objective: To evaluate the current interventions and outcomes in neonates born with hypoplastic left heart syndrome (HLHS) and congenital diaphragmatic hernias (CDHs). Methods: A comprehensive search of the literature using relevant search words was conducted from the date of each database inception to August 2018 to identify interventions and outcomes in patients with CDH and HLHS. Conference papers, review articles, case reports, and animal studies were not eligible for this review. Articles were also excluded if left heart hypoplasia, rather than HLHS, was studied. Neither language nor sample size was used for exclusion. A preliminary screening of article titles was performed to rule out irrelevant articles and article types by a single reviewer. A second screening circle was performed by two independent reviewers to assess remaining abstracts. Data were presented as a systematic review and were descriptively summarized. Results: Of the 162 retrieved articles, five studies were eligible for inclusion. The total number of neonates included in this systematic review was 5063. One hundred and eighteen (2.3%) presented specifically with CDH and HLHS. Overall, a total of 62 of the 118 patients underwent a surgical procedure (51%) with 36 (59%) surviving to discharge. Conclusions: Available data suggest current surgical interventions still result in a high degree of mortality. Age at which surgery occurred, pulmonary function and the use of extra-corporeal membrane oxygenation (ECMO) are potential variables that may determine and improve outcomes in these patients in the future. However, long-term outcomes and analyses of more variables are needed to determine effective treatment for this rare but often fatal comorbid congenital diagnosis.
Keywords: congenital diaphragm hernia; extracorporeal oxygenation; female; fetal therapy; fetus; fetus echography; fetus malformation; human; hypoplastic left heart syndrome; language; lung function; male; mortality; newborn; review; sample size; surgical technique; systematic review

Comprehensive MRI assessment of the cardiovascular responses to food ingestion in Fontan physiology - Hauser, J.A.; Jones, A.; Pandya, B.; Taylor, A.M.; Muthurangu, V. (American Journal of Physiology - Heart and Circulatory Physiology, 2020)
In univentricular (Fontan) physiology, peripheral and splanchnic vascular tone may be raised to counteract reduced cardiac output (CO) and elevated central venous pressure and thus maintain vital organ perfusion. This could negatively affect the normal cardiovascular response to food ingestion, where mesenteric vasodilation and a concurrent rise in CO are central. We sought to elucidate this using rapid cardiovascular MRI. Thirty fasting subjects (50% controls, 40% women and 60% men) ingested a standardized meal. Responses over ~50 min in mean arterial pressure (MAP), CO, and blood flow in all major aortic branches were measured, and regional vascular impedance (Z0) was calculated. Differences from baseline and between groups were assessed by repeated-measures mixed models. Compared with the control group, the Fontan patient group had greater fasting Z0 of the legs and kidneys, resulting in greater systemic Z0 and similar MAP. They further had similar blood flow to the digestive organs at baseline, despite larger variation in mesenteric resistance. Postprandially, blood flow to the legs decreased in the control group but not in the Fontan patient group. Increases in CO and superior mesenteric blood flow were similar in both groups, but the celiac response was blunted in the Fontan patient group. No significant differences in MAP responses were observed. In conclusion, alterations in vascular tone to counteract adverse hemodynamics and raised hepatic afterload may blunt vasoreactivity in the legs and the celiac axis in Fontan physiology. Further study is needed to determine whether blunted celiac or mesenteric vasoreactivity is linked to deteriorating hemodynamics and poor prognosis in Fontan patients. NEW & NOTEWORTHY Novel data on cardiovascular physiology in response to a meal in Fontan patients are presented. Using a previously validated dynamic MRI protocol, we demonstrated that the usual increase in cardiac output and the dilation of the superior mesenteric artery are preserved in clinically well Fontan patients. In contrast, vasoconstriction of the legs may have prevented redistribution of blood flow from this region in response to the meal. This may also affect responses to other types of stress. Celiac vasodilation was also absent in Fontan patients. This may be due to abnormal hepatic circulation. The proposed protocol may be used to study Fontan complications secondary to abnormal regional hemodynamics.
Keywords: adolescent; adult; artery resistance; article; blood flow; cardiovascular response; clinical assessment; controlled study; fasting; female; fontanel; food intake; heart afterload; heart output; hemodynamics; human; human experiment; male; mean arterial pressure; mesenteric artery; nuclear magnetic resonance imaging; postprandial state; priority journal

Morbidity and mortality of very low birth weight infants with congenital heart disease - Song, W.S.; Kim, C.Y.; Lee, B.S.; Kim, E.A.-R.; Kim, K.-S.; Jung, E. (Korean Circulation Journal, 2020)
Background and Objectives: This study aimed to provide morbidity and mortality information on very low birth weight (VLBW) infants with congenital heart disease (CHD-VLBWs). Methods: The study used a 10-year cohort of VLBW infants from a single institution. CHD was classified according to International Classification of Diseases, Version 9, Clinical Modification. Mortality and neonatal outcomes were assessed by comparing the CHD-VLBWs with gestational age- and birth weight-matched controls. Results: The prevalence of CHD-VLBWs was 7.5% (79/1,050), mean gestational age was 31.1±3.2 weeks, and mean birth weight was 1,126.2±268.3 g; 50.6% of the infants were small for the gestational age. The CHD-VLBWs more commonly had bronchopulmonary dysplasia (BPD), and the longer they were exposed to oxygen, the more frequently they developed BPD. Those with cyanotic heart disease developed severe BPD more frequently. Necrotizing enterocolitis (NEC) occurred frequently in the CHD-VLBWs and was not associated with their feeding patterns. CHD-VLBWs had a higher mortality rate; prematurity-related diseases were the leading cause of death before surgery, while heart-related problems were the leading cause of death after surgery. We found no significant difference in mortality from prematurity-related disease between the CHD-VLBWs and controls. In the subgroup analysis of CHD, the cyanotic CHD group had a higher incidence of BPD and higher mortality rate than the acyanotic CHD group. Conclusions: CHD-VLBWs showed higher BPD, NEC, and mortality rates than those without CHD. There was also a higher incidence of BPD and mortality in VLBW infants with cyanotic CHD than in those with acyanotic CHD.
Keywords: information processing device; mechanical ventilator; SPSS 22.0; prostaglandin E1; steroid; surfactant; adult; aortic coarctation; aortopulmonary shunt; article; artificial ventilation; atrioventricular septal defect; birth weight; cause of death; clinical study; cohort analysis; congenital heart disease; cyanotic heart disease; data analysis software; Ebstein anomaly; Fallot tetralogy; feeding behavior; female; gestational age; great vessels transposition; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; human; hypoplastic left heart syndrome; ICD-9-CM; low level laser therapy; lung artery banding; lung dysplasia; major clinical study; male; mortality rate; necrotizing enterocolitis; newborn; newborn morbidity; newborn mortality; oxygen therapy; patent ductus arteriosus; prematurity; prevalence; pulmonary valve atresia; pulmonary valve stenosis; pulmonary valvuloplasty; retrolental fibroplasia; retrospective study; risk factor; small for date infant; surgical mortality; very low birth weight; SPSS 22.0

Hyaluronidase-facilitated high-dose subcutaneous igg effectively controls parvovirus b19 infection in a pediatric cardiac transplant patient with severe t-cell lymphopenia - Cruz, R.J.; Dasso, J.F.; Duff, C.; Krasnopero, D.; Long, Z.; Ellison, M.; Nieves, D.; Sriaroon, P.; Asante-Korang, A.; Walter, J.E. (Open Forum Infectious Diseases, 2020)
We treated three pediatric cardiac transplant patients with chronic parvovirus viremia with high-dose intravenous immunoglobulin (HD-IVIG). One patient with severe T-cell lymphopenia suffered recurrent viremia and aseptic meningitis, which resolved remarkably when he was switched to highdose hyaluronidase-facilitated subcutaneous immunoglobulin (HD-SCIG-Hy). We discuss the advantages of HD-SCIG-Hy vs HD-IVIG treatment for similar cases.
Keywords: hemoglobin; hyaluronidase; immunoglobulin G; mycophenolic acid; prednisone; rapamycin; tacrolimus; thymocyte antibody; adult; antiretroviral therapy; article; case report; CD4 lymphocyte count; CD8+ T lymphocyte; child; chronic kidney failure; clinical article; drug administration route; drug dose increase; drug megadose; drug substitution; drug withdrawal; erythema infectiosum; human; hypoplastic left heart syndrome; immunomodulation; immunosuppressive treatment; lymphocytopenia; male; meningitis; patient history of heart transplantation; posttransplant lymphoproliferative disease; proteinuria; pulmonary valve atresia; quality of life; school child; T lymphocyte; virus load; young adult

Influence of Offset on Hemodynamics of Intra-atrial Conduit Fontan's Procedure and Its Clinical Implications - Hu, J.; Wang, Q.; Tong, Z.; Shen, J.; Liu, J.; Sun, Y.; Zhang, H. (Thoracic and Cardiovascular Surgeon, 2020)
Background The desirable distance, defined as offset, between the central line of the superior vena cava (SVC) and the intra-atrial conduit after an intra-atrial conduit (IAC) Fontan's procedure remained unclear. We compared the hemodynamic features using virtual surgery with different offset designs in our study. Methods Three-dimensional models of IAC Fontan's procedure were reconstructed according to the magnetic resonance imagings (MRIs) of three patients, then four models for each patient with different offsets equaling 100, 67, 33, and 0% of the diameter of the IVC were reconstructed. Computational fluid dynamics (CFD) were performed in each model to predict the best hemodynamic features, including streamlines of blood flow, wall shear stress (WSS), energy loss (EL), and the hepatic flow distribution (HFD) ratio. Results Comprehensive evaluation of WSS, EL, and HFD revealed than an offset of 33% presents the best hemodynamic performance among the three patients modeled. In patient A, an offset of 33% resulted in the best HFD (left pulmonary artery/right pulmonary artery [LPA/RPA] = 35/65%). In patient B, the best trade-off between HFD (35/65%), and WSS was achieved with an offset of 33%. In patient C, EL peaked at an offset of 0% and significantly dropped at an offset of 33% with a desirable HFD (60/40%). Conclusions We verified that the offset distance influences hemodynamic performance in IAC Fontan's procedure. Considering several hemodynamic parameters, the best trade-offs between hemorheology, pulmonary perfusion, and energy efficiency were achieved at an offset of 33%. This distance should be taken into consideration and optimized during the surgical planning for the IAC Fontan's procedure.
Keywords: polytetrafluoroethylene implant; adolescent; article; blood flow; clinical article; clinical outcome; computational fluid dynamics; computer aided design; congenital heart disease; female; Fontan procedure; heart atrium septum defect; heart cycle; heart right ventricle double outlet; heart single ventricle; hemodynamic parameters; hemodynamics; human; image reconstruction; intra atrial conduit Fontan procedure; left pulmonary artery; liver blood flow; lung blood vessel; lung resistance; male; nuclear magnetic resonance imaging; priority journal; pulmonary artery; pulmonary valve stenosis; right pulmonary artery; shear stress; superior cava vein; viscosity

Provider perspective on the role of palliative care in hypoplastic left heart syndrome - Lowenstein, S.; MacAuley, R.; Perko, K.; Ronai, C. (Cardiology in the Young, 2020)
Objective: Hypoplastic left heart syndrome is a single ventricle defect. While staged surgical palliative treatments have revolutionised care, patients with hypoplastic left heart syndrome continue to have significant morbidity and mortality. In 2017, the National Pediatric Cardiology Quality Improvement Collaborative recommended all single ventricle patients to receive a prenatal palliative care consult. This study aimed to elucidate provider perspectives on the implementation of prenatal palliative care consults for families expecting a child with hypoplastic left heart syndrome.Methods: An online survey was administered to obstetric and paediatric providers of relevant disciplines to assess their experience with palliative care involvement in hypoplastic left heart syndrome cases.Results: Nearly, all physicians (97%) and most registered nurses (79%) agreed that the initial palliative care consult for patients with hypoplastic left heart syndrome should occur during the prenatal period. Respondents also indicated that prenatal palliative care consults should also be offered in a variety of other CHD conditions. Participants believed positive aspects of this new referral protocol included an expanded support network for families, decreased family stress during the postnatal period, increased patient education about what to expect during the postnatal period, and continuity of care.Conclusion: Multidisciplinary healthcare professionals believe that prenatal palliative care consults provide a variety of benefits for patients and families with hypoplastic left heart syndrome. Additional, multi-centre research is necessary to evaluate whether prenatal palliative care consults should become standard of care for families expecting a child with a single ventricle defect.
Keywords: article; congenital heart disease; consultation; family stress; human; hypoplastic left heart syndrome; palliative therapy; patient education; patient referral; physician; prenatal care; psychosocial care; registered nurse; transitional care

Health-related quality of life for children and adolescents in school age with hypoplastic left heart syndrome: A single-centre study - Oberhuber, R.D.; Huemer, S.; Mair, R.; Sames-Dolzer, E.; Kreuzer, M.; Tulzer, G. (Cardiology in the Young, 2020)
Data from neurological and radiological research show an abnormal neurological development in patients treated for hypoplastic left heart syndrome. Thus, the aim of this study was to survey the quality of life scores in comparison with healthy children and children with other heart diseases (mild, moderate, and severe heart defects, heart defects in total). Children with hypoplastic left heart syndrome (aged 6.3-16.9 years) under compulsory education requirements, who were treated at the Children's Heart Center Linz between 1997 and 2009 (n = 74), were surveyed. Totally, 41 children and 44 parents were examined prospectively by psychologists according to Pediatric Quality of Life Inventory, a health-related quality of life measurement. The results of the self-assessments of health-related quality of life on a scale of 1-100 showed a wide range, from a minimum of 5.00 (social functioning) to a maximum of 100 (physical health-related summary scores, emotional functioning, school functioning), with a total score of 98.44. The parents' assessments (proxy) were quite similar, showing a range from 10 (social functioning) up to 100. Adolescent hypoplastic left heart syndrome patients rated themselves on the same level as healthy youths and youths with different heart diseases. The results show that patients with hypoplastic left heart syndrome aged 6-16 years can be successfully supported and assisted in their psychosocial development even if they show low varying physical and psychosocial parameters. The finding that adolescent hypoplastic left heart syndrome patients estimated themselves similar to healthy individuals suggests that they learnt to cope with a severe heart defect.
Keywords: adolescence; adolescent; article; child; controlled study; education; female; follow up; heart center; human; hypoplastic left heart syndrome; juvenile; major clinical study; male; Pediatric Quality of Life Inventory; preschool child; psychologist; psychosocial development; quality of life; social interaction

Standardization of the perioperative management for neonates undergoing the norwood operation for hypoplastic left heart syndrome and related heart defects - Natarajan, S.S.; Stagg, A.; Taylor, A.M.; Griffis, H.M.; Bosler, C.K.; Cates, M.; Dewitt, A.G.; Giglia, T.M.; Mascio, C.E.; Ravishankar, C.; Rossano, J.W.; Taylor, L.C.; et al. (Pediatric Critical Care Medicine, 2020)
Objectives: In-hospital complications after the Norwood operation for single ventricle heart defects account for the majority of morbidity and mortality. Inpatient care variation occurs within and across centers. This multidisciplinary quality improvement project standardized perioperative management in a large referral center. Design: Quality improvement project. Setting: High volume cardiac center, tertiary care children's hospital. Patients: Neonates undergoing Norwood operation. Interventions: The quality improvement team developed and implemented a clinical guideline (preoperative admission to 48 hr after surgery). The composite process metric, Guideline Adherence Score, contained 13 recommendations in the guideline that reflected consistent care for all patients. Measurements and Main Results: One-hundred two consecutive neonates who underwent Norwood operation (January 1, 2013, to July 12, 2016) before guideline implementation were compared with 50 consecutive neonates after guideline implementation (July 13, 2016, to May 4, 2018). No preguideline operations met the goal Guideline Adherence Score. In the first 6 months after guideline implementation, 10 of 12 operations achieved goal Guideline Adherence Score and continued through implementation, reaching 100% for the last 10 operations. Statistical process control analysis demonstrated less variability and decreased hours of postoperative mechanical ventilation and cardiac ICU length of stay during implementation. There were no statistically significant differences in major hospital complications or in 30-day mortality. A higher percentage of patients were extubated by postoperative day 2 after guideline implementation (67% [30/47] vs 41% [41/99], respectively; p = 0.01). Of these patients, reintubation within 72 hours of extubation significantly decreased after guideline implementation (0% [0/30] vs 17% [7/41] patients, respectively; p = 0.02). Conclusions: This initiative successfully implemented a standardized perioperative care guideline for neonates undergoing the Norwood operation at a large center. Positive statistical process control centerline shifts in Guideline Adherence Score, length of postoperative mechanical ventilation, and cardiac ICU length of stay were demonstrated. A higher percentage were successfully extubated by postoperative day 2. Establishment of standard processes can lead to best practices to decrease major adverse events.
Keywords: article; artificial ventilation; child; complication; controlled study; coronary care unit; extubation; female; heart center; human; hypoplastic left heart syndrome; length of stay; major clinical study; male; mortality; newborn; Norwood procedure; perioperative period; practice guideline; process control; protocol compliance; standardization; tertiary health care; total quality management

Impact of protein-losing enteropathy in children who underwent the Fontan operation - Alkofair, B.; Alruwaili, A.; Gai, J.; Harahsheh, A.S. (Cardiology in the Young, 2020)
Previous reports have identified risk factors associated with development of post-Fontan protein-losing enteropathy. Less is known about the economic impact and resource utilisation required for post-Fontan protein-losing enteropathy in the current era. We conducted a single-centre retrospective study to assess the impact of post-Fontan protein-losing enteropathy on transplant-free survival. We also described resource utilisation and treatment variations among post-Fontan protein-losing enteropathy patients. Children who received care at our centre between 2009 and 2017 after the Fontan surgery were eligible. Initial admissions for the Fontan operative procedure were excluded. Demographics, hospital admissions, resource utilisation, medications and charges were reviewed. Patients were divided into two groups based on the presence of post-Fontan protein-losing enteropathy. Of the 343 patients screened, 147 met the eligibility criteria. Of these, 28 (19%) developed protein-losing enteropathy. After adjusting for follow-up duration, the protein-losing enteropathy group had higher number of encounters (2.15 ± 2.16 versus 1.47 ± 2.56, p 0.002), hospital length of stay (days) (25 ± 51.3 versus 11.4 ± 41.7, p < 0.0001) and total charges (2018US$) (388,489 ± 759,859 versus 202,725 ± 1,076,625, p < 0.0001). Encounters for patients with protein-losing enteropathy utilised more therapies. Among those with protein-losing enteropathy, use of digoxin was associated with slightly decreased odds for mortality and/or transplant (0.95, confidence interval 0.90-0.99, p 0.021). The 10-year transplant-free survival for patients with/without protein-losing enteropathy was 65.7/97.3% (p 0.002), respectively. Post-Fontan protein-losing enteropathy is associated with reduced 10-year transplant-free survival, higher resource utilisation, charges and medication use compared with the non-protein-losing enteropathy group. Practice variation among post-Fontan protein-losing-enteropathy patients is common. Further larger studies are needed to assess the impact of standardisation on the well-being of children with post-Fontan protein-losing enteropathy.
Keywords: article; child; controlled study; demography; female; follow up; Fontan procedure; health economics; heart single ventricle; heart surgery; hospital admission; human; length of stay; major clinical study; male; mortality; protein losing gastroenteropathy; retrospective study; standardization; surgery; transplant free survival; wellbeing; digoxin

Optimism despite profound uncertainty: School and social relationships in adolescents with single ventricle heart disease - Peterson, J.K.; Olshansky, E.F.; Guo, Y.; Evangelista, L.S.; Pike, N.A. (Cardiology in the Young, 2020)
Background: Survivors of single ventricle heart disease must cope with the physical, neurodevelopmental, and psychosocial sequelae of their cardiac disease, which may also affect academic achievement and social relationships. The purpose of this study was to qualitatively examine the experiences of school and social relationships in adolescents with single ventricle heart disease. Methods: A descriptive phenomenological methodology was employed, utilising semi-structured interviews. Demographic and clinical characteristics were obtained via chart review. Results: Fourteen adolescents (aged 14 to 19 years) with single ventricle heart disease participated. Interviews ranged from 25 to 80 minutes in duration. Four themes emerged from the interviews, including "Don't assume": Pervasive ableism; "The elephant in the room": Uncertain future; "Everyone finds something to pick on": Bullying at school; "They know what I have been through": Social support. The overall essence generated from the data was "optimism despite profound uncertainty."Conclusions: Adolescents with single ventricle heart disease identified physical limitations and school challenges in the face of an uncertain health-related future. Despite physical and psychosocial limitations, most remained optimistic for the future and found activities that were congruent with their abilities. These experiences reflect "optimism despite profound uncertainty.
Keywords: academic achievement; adolescent; adult; article; bullying; clinical article; clinical feature; demography; elephant; female; Fontan procedure; heart single ventricle; human; male; medical record review; nonhuman; optimism; peer group; qualitative research; semi structured interview; social interaction; social support; uncertainty

Covid-19 in an infant with systemic to pulmonary artery shunt dependent functionally univentricular physiology - Loomba, R.S.; Lee, B.; Phillips, M.; Vricella, L.; Wong, J. (Cardiology in the Young, 2020)
We report a case of two-month old with a functionally univentricular heart and parallel circulation who presented to the emergency department with Covid-19 and subsequently developed acute respiratory distress syndrome. The course of illness, clinical values, and laboratory markers are characterized in this report.
Keywords: adult respiratory distress syndrome; article; case report; clinical article; coronavirus disease 2019; emergency ward; female; heart single ventricle; human; infant; male; systemic pulmonary shunt

Clinical outcome of prenatally suspected cardiac rhabdomyomas of the fetus - Altmann, J.; Kiver, V.; Henrich, W.; Weichert, A. (Journal of perinatal medicine, 2019)
Background The main objective of this retrospective analysis in a large tertiary center was the clinical outcome of prenatally diagnosed cardiac rhabdomyomas as well as the identification of factors influencing fetal prognosis. Methods A total of 45 cases of fetuses with prenatally suspected rhabdomyoma and their clinical outcome were analyzed retrospectively. A review of the literature was also performed. Results In five cases, after a tuberous sclerosis complex (TSC) mutation had been confirmed, termination of pregnancy was chosen. In 30 cases postnatal data were available. In 93% TSC was confirmed clinically or by mutational analysis. Two thirds of fetuses presented with multiple tumor while one third presented with a solitary tumor. In two fetuses mild pericardial effusions were observed. Another three fetuses presented with extrasystoles prenatally. No hydrops fetalis or fetal perinatal demise were observed. After birth 41% of the children suffered from arrhythmia including supra- and ventricular tachycardia, Wolff-Parkinson-White syndrome and atrioventricular block. One child received a Fontan procedure with Glenn anastomosis. Another child with a dilatative cardiomyopathy and a left ventricular ejection fraction of 15% died. Fifty-two percent of the children with TSC suffered from epilepsy ranging from absence epilepsy and West syndrome to generalized seizures with a frequency of up to 40 per day. Two children underwent neurosurgery to remove the epileptogenic focus. One child suffered from TSC and Lesch-Nyhan disease. In another case Beckwith-Wiedemann syndrome was identified as the causative disorder. Conclusion Rhabdomyoma are rare, benign tumors. There is an association with TSC. In the majority of cases rhabdomyoma are not hemodynamically relevant and do not increase in size. The quality of life of affected patients is impaired particularly due to epilepsy and psychomotor retardation.
Keywords: adolescent; adult; complication; diagnostic imaging; female; fetus disease; fetus echography; heart tumor; human; pregnancy; retrospective study; rhabdomyoma; tuberous sclerosis; young adult

Early Neurodevelopmental Outcomes in Children with Hypoplastic Left Heart Syndrome and Related Anomalies After Hybrid Procedure - Khalid, O.M.; Harrison, T.M. (Pediatric Cardiology, 2019)
The hybrid strategy is one approach to single ventricle palliation. In this study, we reported neurodevelopment at 12 months for two cohorts of children managed with the hybrid and clinical factors associated with neurodevelopment in the entire sample. We performed a retrospective study of children with single ventricle who had undergone a neonatal hybrid procedure. One group included infants with hypoplastic left heart syndrome (HLHS); another group included infants with non-HLHS single ventricle. Neurodevelopment was assessed with 12-month Bayley III. Parametric and non-parametric statistics were used for analysis. Nine infants with HLHS and 15 with non-HLHS were identified. Abnormal neurodevelopment was identified in 11 of 24 (46%), primarily motor (46%). Development did not differ between groups. In the whole sample, higher lactate levels were associated with lower cognitive scores (p = 0.04). Fewer mechanical ventilation days were associated with higher cognitive scores (p = 0.05) after Stage 1 and higher motor scores after Stage 2. Shorter ICU length of stay (p = 0.01), shorter hospital length of stay (p = 0.01), and fewer complications (p = 0.01) after stage 2 were associated with higher motor scores. Higher cognitive (p = 0.02) and language (p = 0.002) scores were associated with higher weight at 12 months. In the largest cohort of single ventricle children treated with neonatal hybrid palliation yet reported, significant neurodevelopmental impairment was identified. No differences in neurodevelopment were found between children with HLHS and those with non-HLHS variants. A multicenter trial is needed to test differences in neurodevelopment between hybrid and Norwood approaches.
Keywords: lactic acid; article; artificial ventilation; body weight; clinical article; cognitive development; developmental delay; heart single ventricle; heart surgery; human; hybrid procedure; hypoplastic left heart syndrome; infant; language development; length of stay; longitudinal study; motor development; neonatal intensive care unit; Norwood procedure; retrospective study; risk factor; surgical technique

Outcome of patients with functional single ventricular heart after pacemaker implantation: What makes it poor, and what can we do? - Kodama, Y.; Kuraoka, A.; Ishikawa, Y.; Nakamura, M.; Ushinohama, H.; Sagawa, K.; Umemoto, S.; Hashimoto, T.; Sakamoto, I.; Ohtani, K.; Ide, T.; Tsutsui, H.; et al. (Heart Rhythm, 2019)
Background: Pacemaker implantation in patients with single ventricle is associated with poor outcomes. Objective: The purpose of this study was to determine the reasons for the poor outcomes of pacemaker implantation. Methods: We performed a retrospective chart review of patients with single ventricle who had undergone permanent pacemaker implantation. Patients were categorized into 3 groups based on the site of pacing and the proportion of ventricular pacing (VP) as follows: (1) atrial pacing group with atrial pacing only (n = 11); (2) low VP group with low daily VP proportion (<50%; n = 12); and (3) high VP group with high daily VP proportion (≥50%; n = 15). Pacing leads were placed at the epicardium in all patients. Results: No patients in the atrial pacing or low VP groups died, whereas the survival rate in the high VP group was 58.9% and 39.3% at 10 and 20 years, respectively, after pacemaker implantation. Among the post-Fontan patients, plasma brain natriuretic peptide (BNP) levels significantly increased with the proportion of VP: 11.7, 20.3, and 28.4 pg/mL in the atrial pacing, low VP, and high VP groups, respectively (P = 0.04). In the high VP group, the plasma BNP level was significantly lower in patients with an apical pacing lead than in those with a nonapical pacing lead (27.0 pg/mL vs 82.8 pg/mL, respectively; P = .03). Conclusion: A higher proportion of VP was associated with poor outcome and higher plasma BNP levels, probably due to ventricular dyssynchrony. In epicardial ventricular pacing, apical pacing is better to avoid the increase in ventricular stress and plasma BNP level.
Keywords: brain natriuretic peptide; apical pacing; article; cardiac resynchronization therapy; child; epicardial ventricular pacing; epicardium; female; Fontan procedure; heart atrium pacing; heart pacing; heart single ventricle; heart ventricle function; Holter monitoring; human; major clinical study; male; medical record review; pacemaker implantation; preschool child; priority journal; protein blood level; treatment outcome

Percutaneous embolization of lymphatic fistulae as treatment for protein-losing enteropathy and plastic bronchitis in patients with failing Fontan circulation - Maleux, G.; Storme, E.; Cools, B.; Heying, R.; Boshoff, D.; Louw, J.J.; Frerich, S.; Malekzadeh-Milanii, S.; Hubrechts, J.; Brown, S.C.; Gewillig, M. (Catheterization and Cardiovascular Interventions, 2019)
Background: To determine the feasibility and clinical result of selective embolization of hepatoduodenal or paratracheal lymphatics in Fontan patients with protein-losing enteropathy (PLE) or plastic bronchitis (PB). Methods: Dilated lymph vessels in periportal (PLE) or paratracheal (PB) position were percutaneously punctured with a 22G Chiba needle. Intralymphatic position was confirmed by water soluble contrast injection with drainage to hepatoduodenal or tracheal fistulae. After flushing with 10% glucose solution, occlusion of hepatoduodenal or paratreacheal lymphatics was effected by injection of 1–4 cc mixture 4/1 of Lipiodol/n-butyl cyanoacrylate (n-BCA; Histoacryl). Results: Seven patients with proven PLE were treated with periportal lymphatic embolization 10.7 (range: 6.6–13.5) years after the Fontan operation. The Fontan operation was performed at a median age of 3.7 (range: 2.9–5.7) years and PLE started a median of 3.1 (range: 0.9–4.7) years later. Five patients required a second procedure 2–8 months later. Complications were limited (spillage of glue in portal branch, transient cholangitis, and caustic duodenal bleeding). Six of seven patients reported significant improvement in quality of life and normalization of albumin levels after limited follow-up (p <.01). One patient (Fontan at 2.9 years; age 16.4 years) had PB for 2 years. Selective transthoracic cone-beam-directed puncture of left and right paratracheal lymphatics with n-BCA embolization of distal lymphatic fistulae resulted in lasting absence of tracheal casts (11 months). Conclusions: Embolization of periportal/peritracheal lymphatics is a promising technique in Fontan patients with PLE/PB. Larger series are required to determine incidence and reasons of success/failure, with long-term results and effects on liver function.
Keywords: Chiba needle; albumin; adolescent; article; artificial embolization; bronchitis; child; cholangitis; clinical article; computer assisted tomography; duodenum bleeding; feasibility study; fistula; Fontan procedure; human; liver parenchyma; protein losing gastroenteropathy; quality of life; retrospective study

Results of surgery on adults with functional single ventricle without prior cardiac surgery in childhood - Yang, J.; He, B.-C.; Chen, J.-M.; Cen, J.-Z.; Wen, S.-S.; Xu, G.; Zhuang, J. (Journal of Cardiac Surgery, 2019)
Objectives: Patients with unoperated functional single ventricle (FSV) rarely survive into adulthood with good functional status and there are few reports about surgical results of adult patients with FSV. This study retrospectively reviews our experience with surgery in adult patients with FSV. Methods: From January 2008 to September 2017, 65 adult patients with FSV underwent surgery in our hospital. Twenty underwent Blalock-Taussig shunt or bidirectional Glenn procedures in other hospitals prior, and four were lost to follow-up. Finally, 41 patients were included in this study. Results: The early postoperative mortality was 7.3% (3/41). Postoperative systemic arterial oxygen saturation (SpO2, 83.7% ± 4.8%) was significantly higher than preoperative SpO2 (77.9% ± 10.1%, P <.01). The mean follow-up time was 3.9 ± 3.1 years (range 1-11 years). There was only one case of late mortality and massive hemoptysis was the cause of death. Right ventricular morphology and severe atrioventricular valve regurgitation (AVVR) were the risk factors of postoperative death for patients with pulmonary stenosis(PS). There was no death case in patients who received Fontan procedure. In a follow-up, we found the grade of AVVR was reduced and the grade of heart function (New York Heart Association) was improved. Conclusions: Adult patients with FSV can also undergo surgery. The mortality was acceptable and late results were satisfactory. After surgery, oxygen saturations increased, grades of AVVR decreased and the heart functions improved. Right ventricular morphology and severe AVVR were risk factors for patients with PS.
Keywords: adult; arterial oxygen saturation; article; Blalock Taussig shunt; clinical article; disease severity; female; follow up; Glenn shunt; heart function; heart right ventricle; heart single ventricle; heart valve regurgitation; hemoptysis; human; male; medical history; New York Heart Association class; outcome assessment; patient satisfaction; postoperative complication; postoperative period; preoperative evaluation; pulmonary valve stenosis; retrospective study; risk factor; surgical mortality; survival rate; young adult

Paternal-age-related de novo mutations and risk for five disorders - Taylor, J.L.; Debost, J.-C.P.G.; Morton, S.U.; Wigdor, E.M.; Heyne, H.O.; Lal, D.; Howrigan, D.P.; Bloemendal, A.; Larsen, J.T.; Kosmicki, J.A.; Weiner, D.J.; Homsy, J.; et al. (Nature Communications, 2019)
There are established associations between advanced paternal age and offspring risk for psychiatric and developmental disorders. These are commonly attributed to genetic mutations, especially de novo single nucleotide variants (dnSNVs), that accumulate with increasing paternal age. However, the actual magnitude of risk from such mutations in the male germline is unknown. Quantifying this risk would clarify the clinical significance of delayed paternity. Using parent-child trio whole-exome-sequencing data, we estimate the relationship between paternal-age-related dnSNVs and risk for five disorders: autism spectrum disorder (ASD), congenital heart disease, neurodevelopmental disorders with epilepsy, intellectual disability and schizophrenia (SCZ). Using Danish registry data, we investigate whether epidemiologic associations between each disorder and older fatherhood are consistent with the estimated role of dnSNVs. We find that paternal-age-related dnSNVs confer a small amount of risk for these disorders. For ASD and SCZ, epidemiologic associations with delayed paternity reflect factors that may not increase with age.
Keywords: article; atrioventricular septal defect; autism; congenital blood vessel malformation; congenital heart disease; de novo single nucleotide variant; effect size; epilepsy; father; gene mutation; genetic association; genetic risk; heart atrium septum defect; heart left ventricle outflow tract obstruction; heart right ventricle outflow tract obstruction; heart single ventricle; heart ventricle septum defect; human; ICD-10; incidence; intellectual impairment; medical ethics; mental disease; morbidity; null hypothesis; paternal age; phenotype; progeny; schizophrenia; single nucleotide polymorphism; tricuspid valve disease; whole exome sequencing; whole genome sequencing

Computational fluid dynamic simulations of a cavopulmonary assist device for failing Fontan circulation - Lin, W.C.P.; Doyle, M.G.; Roche, S.L.; Honjo, O.; Forbes, T.L.; Amon, C.H. (Journal of Thoracic and Cardiovascular Surgery, 2019)
Objectives: Adult patients who have undergone the Fontan procedure are highly vulnerable to gradual, progressive circulatory failure, and options to reverse this situation are few. A cavopulmonary assist device could decongest the venous and lymphatic systems, overcome elevated pulmonary vascular resistance, increase cardiac output, and support some of these patients to heart transplant. This study characterizes the performance and challenges of a novel multilumen cannula coupled to an external blood pump proposed as a potential Fontan cavopulmonary assist strategy. Methods: Computational fluid dynamic simulations were conducted for 3 extracardiac Fontan geometries consisting of 1 idealized model and 2 patient-specific models. A range of physiologic flow rates and pump assist levels were simulated to calculate the pressure gain provided by the multilumen cannula. Hemolysis index was estimated for the idealized model with Lagrangian particle tracking and 2 variations of the power-law. Wall shear stresses were also examined. Results: Pressure gains up to 4 and 9 mm Hg were achieved for the idealized and patient-specific models, respectively. Pressure gains increased with both higher cardiac output and larger pump intake through the external pump. Flow-weighted hemolysis show hemoglobin damage levels to be several times lower than the 2% threshold at the highest pump intake flow cases. Wall shear stress predictions depict elevated areas in the pulmonary vessels and regions of the cannula device. Conclusions: The cannula tested in this study shows promise as a percutaneous option to bridge support in some patients with a failing extracardiac Fontan. Limitations identified will be addressed in future design iterations and in ongoing experimental tests.
Keywords: blood pump; cannula; cavopulmonary assist device; heart assist device; mercury; adult; article; assisted circulation; cardiovascular magnetic resonance; cavopulmonary connection; circulation; computational fluid dynamics; computer simulation; female; flow rate; Fontan procedure; heart graft; heart output; heart ventricle enddiastolic pressure; hemolysis; human; inferior cava vein; left pulmonary artery; lung blood vessel; lung vascular resistance; male; priority journal; right pulmonary artery; shear stress; superior cava vein; young adult

Parenting stress trajectories during infancy in infants with congenital heart disease: Comparison of single-ventricle and biventricular heart physiology - Golfenshtein, N.; Hanlon, A.L.; Deatrick, J.A.; Medoff-Cooper, B. (Congenital Heart Disease, 2019)
Objective: Parents of infants with congenital heart disease (CHD) experience increased parenting stress levels, potentially interfering with parenting practices and bear adverse family outcomes. Condition severity has been linked to parenting stress. The current study aimed to explore parenting stress trajectories over infancy in parents of infants with complex CHD, and to compare them by post-operative cardiac physiology. Design: Data from a larger prospective cohort study was analyzed using longitudinal mixed-effects regression modeling. Setting: Cardiac intensive care unit and outpatient clinic of a 480-bed children's hospital in the American North-Atlantic region. Participants: Parents of infants with complex CHD (n = 90). Measures: Parenting stress was measured via the parenting stress index-long form over four time points during infancy. Results: Parents of infants with a single-ventricle heart experienced a decrease in total stress over time. Parents of infants with a biventricular heart experienced a decrease in attachment-related stress, and an increase in stress related to infant temperament over time. Parenting stress trajectories over time significantly differed between groups on infant temperamental subscales. Conclusions: Findings highlight stressful and potentially risky periods for parents of infants with complex CHD, and introduce additional illness-related and psychosocial/familial aspects to the parenting stress concept. Early intervention may promote parental adaptive coping and productive parenting practices in this population.
Keywords: adult; article; biventricular congenital heart disease; child behavior; cohort analysis; congenital heart disease; coronary care unit; disease association; disease severity; emotional attachment; female; heart single ventricle; human; infant; longitudinal study; major clinical study; male; outpatient department; parental stress; pediatric hospital; postoperative period; priority journal; prospective study; stress assessment; temperament

Surveillance and screening practices of New England congenital cardiologists for patients after the Fontan operation - Davey, B.T.; Toro-Salazar, O.H.; Gauthier, N.; Valente, A.M.; Elder, R.W.; Wu, F.M.; Berman, N.; Pollack, P.; Lee, J.H.; Rathod, R.H. (Congenital Heart Disease, 2019)
Introduction: Surveillance and management guidelines for Fontan patients are lacking due to the paucity of evidence in the literature of screening efficacy on outcome measures. Methods: The Fontan Working Group within the New England Congenital Cardiology Association designed an electronic survey to assess surveillance practices for patients with Fontan procedures among New England congenital cardiologists and to explore variability in screening low-risk vs high-risk Fontan patients across regional programs. Results: Fifty-six cardiologists representing 12 regional programs responded to the survey, comprising ~40% of the total New England congenital cardiac physicians. The majority of desired testing and consultation was available within 50 miles of the patient's home institution with some limitations of cardiac catheterization and cardiac magnetic resonance imaging availability. Surveillance and screening were less frequent in low-risk Fontan patients compared to high-risk Fontan patients. Counseling practices were similar for both low-risk and high-risk Fontan patients. Aspirin monotherapy was recommended by 82% of providers for low-risk Fontan patients, while anticoagulation regimens were more varied for the high-risk population. Practitioners with ≤15 years of experience were more likely to provide quality of life testing in both low-risk and high-risk Fontan patients. There were no other major differences in testing frequencies by years of practice, quaternary vs nonquaternary care facility, or the number of Fontan patients in a practice. Conclusion: This survey provides insight into regional practices of screening and surveillance of Fontan patients. These data may be used to design future research studies and evidence-based guidelines to streamline the approach to manage these complex patients.
Keywords: acetylsalicylic acid; anticoagulant agent; beta adrenergic receptor blocking agent; warfarin; adolescent; adult; article; cardiologist; cardiovascular magnetic resonance; child; clinical practice; congenital heart disease; consultation; disease surveillance; evidence based medicine; female; Fontan procedure; health care availability; health care facility; health care survey; health program; heart catheterization; heart ventricle failure; high risk patient; Holter monitoring; human; low risk patient; major clinical study; male; patient counseling; practice guideline; priority journal; quality of life; screening test; United States; work experience

Behavior and quality of life at 6 years for children with hypoplastic left heart syndrome - Goldberg, C.S.; Hu, C.; Brosig, C.; Gaynor, J.W.; Mahle, W.T.; Miller, T.; Mussatto, K.A.; Sananes, R.; Uzark, K.; Trachtenberg, F.; Pizarro, C.; Pemberton, V.L.; et al. (Pediatrics, 2019)
OBJECTIVES:We measured behavioral, quality of life (QoL), and functional status outcomes for 6- year-old children with hypoplastic left heart syndrome enrolled in the Single Ventricle Reconstruction Trial. We sought to compare these outcomes with those in the normative population and to analyze risk factors for worse outcomes within the single-ventricle group. METHODS: Parent-response instruments included the Vineland Adaptive Behavior Scales, Second Edition (Vineland-II) (primary outcome), Behavior Assessment System for Children 2, Pediatric Quality of Life Inventory 4.0, and other measures of QoL and functional status. We compared subjects with those in the normative sample using 1-sample Wilcoxon rank tests and assessed outcome predictors using multivariable regression. RESULTS: Of 325 eligible patients, 250 (77%) participated. Compared with population norms, participants had lower scores on the Vineland-II motor skills domain (90 6 17 vs 100 6 15; P <001), with 11% scoring .2 SDs below the normative mean. On nearly all major domains, more study subjects (3.3%-19.7%) scored outside the normal range than anticipated for the general population. Independent risk factors for lower Vineland-II scores included perioperative extracorporeal membrane oxygenation, male sex, use of regional cerebral perfusion, catheterization after stage 2 operation, visual problems, seizure history, and more complications after 2 years (R2 = 0.32). Independent predictors of worse Behavior Assessment System for Children 2 (R2 = 0.07-0.20) and Pediatric Quality of Life Inventory 4.0 (R2 = 0.17-0.25) domain scores also included sociodemographic factors and measures of morbidity and/or greater course complexity. CONCLUSIONS: At 6 years, children with hypoplastic left heart syndrome had difficulty in areas of adaptive behavior, behavioral symptoms, QoL, and functional status. Principal risks for adverse outcomes include sociodemographic factors and measures of greater course complexity. However, models reveal less than one-third of outcome variance.
Keywords: article; behavior assessment; brain perfusion; catheterization; child; child behavior; demography; extracorporeal oxygenation; female; follow up; functional status; functional status assessment; human; hypoplastic left heart syndrome; major clinical study; male; morbidity; Pediatric Quality of Life Inventory; perioperative period; prediction; preschool child; priority journal; quality of life; quality of life assessment; rating scale; risk factor; scoring system; sex; social status

Five-year survival of infants with major congenital anomalies: a registry based study - Schneuer, F.J.; Bell, J.C.; Shand, A.W.; Walker, K.; Badawi, N.; Nassar, N. (Acta Paediatrica, International Journal of Paediatrics, 2019)
Aim: To determine survival of infants with major congenital anomalies (CA) and assess the effect of co-existing anomalies and gestational age. Methods: All liveborn infants with major CA born in New South Wales (NSW), Australia, 2004–2009 were identified from the NSW Register of Congenital Conditions. Deaths were identified via record linkage to death registrations and five-year survival was estimated using Kaplan–Meier methods. Results: There were 8521 liveborn infants with CA of whom 617 (7.2%) died within the first five years of life. Half of deaths occurred in the first week of life. The overall five-year survival rate was 92.8% (95%CI: 92.2–93.3) and 83.2% (95%CI: 79.0–87.4) for syndromes, 83.4% (95%CI: 80.9–85.9) for multiple, 85.1% (95%CI: 82.6–87.5) for chromosomal, 95.3% (95%CI: 94.8–95.8) for isolated and 96.2% (95%CI: 94.3–98.1) for non-Q chapter anomalies. Five-year survival for chromosomal, syndromes and sub-groups was higher for isolated compared with multiple anomalies ranging from 77.5% to 98.9% and 68.6% to 89.5%, respectively. Survival was lower for preterm (79.4%; 95%CI: 77.5-81.4) than for term infants (95.8%; 95%CI: 95.3–96.3). Conclusion: Nine in ten infants with major CA survive up to five years, although there is variability in survival across CA groups. Survival of infants with major congenital anomalies has improved in recent years.
Keywords: anencephalus; anus atresia; aortic coarctation; aortic valve stenosis; arthrogryposis; article; atrioventricular septal defect; beta thalassemia; bile duct atresia; bladder exstrophy; breast malformation; childhood mortality; choana atresia; cleft lip; cleft lip palate; cleft palate; clubfoot; comorbidity; congenital hypothyroidism; congenital malformation; controlled study; corpus callosum agenesis; craniofacial synostosis; cystic fibrosis; diaphragm hernia; Down syndrome; duodenum atresia; duodenum stenosis; Edwards syndrome; encephalocele; epispadias; esophagus atresia; esophagus fistula; Fallot tetralogy; fetus hydrops; gastroschisis; gestational age; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; Hirschsprung disease; holoprosencephaly; human; hydrocephalus; hydronephrosis; hypoplastic left heart syndrome; hypospadias; kidney agenesis; kidney malformation; kidney polycystic disease; Klinefelter syndrome; limb reduction defect; lung adenoma; lung sequestration; lung vein drainage anomaly; major clinical study; malrotation syndrome; microcephaly; mortality rate; multiple malformation syndrome; neural tube defect; New South Wales; newborn; omphalocele; optic nerve hypoplasia; patent ductus arteriosus; phenylketonuria; polydactyly; Potter syndrome; prematurity; priority journal; prune belly syndrome; pseudohermaphroditism; pulmonary valve stenosis; small intestine disease; spinal dysraphism; spine malformation; survival; survival rate; syndactyly; term birth; thorax malformation; trisomy 13; Turner syndrome; urethra malformation

First trimester combined screening biochemistry in detection of congenital heart defects - Alanen, J.; Korpimaki, T.; Kouru, H.; Sairanen, M.; Leskinen, M.; Gissler, M.; Ryynanen, M.; Nevalainen, J. (Journal of Maternal-Fetal and Neonatal Medicine, 2019)
Objective: To evaluate the performance of first trimester biochemical markers, pregnancy-associated plasma protein-A (PAPP-A), free beta human chorionic gonadotropin (fβ-hCG), and nuchal translucency (NT) in detection of severe congenital heart defects (CHDs). Methods: During the study period from 1 January 2008 to 31 December 2011, biochemical markers and NT were measured in 31,144 women as part of voluntary first trimester screening program for Down’s syndrome in Northern Finland. Data for 71 severe CHD cases and 762 controls were obtained from the hospital records and from the National Medical Birth Register, which records the birth of all liveborn and stillborn infants, and from the National Register of Congenital Malformations that receives information about all the CHD cases diagnosed in Finland. Results: Both PAPP-A and fβ-hCG multiple of median (MoM) values were decreased in all severe CHDs: 0.71 and 0.69 in ventricular septal defects (VSDs), 0.58 and 0.88 in tetralogy of Fallot cases (TOFs), 0.82 and 0.89 in hypoplastic left heart syndromes (HLHSs), and 0.88 and 0.96 in multiple defects, respectively. NT was increased in all study groups except of VSD group. ROC AUC was 0.72 for VSD when combining prior risk with PAPP-A and fβ-hCG. Adding NT did not improve the detection rate. With normal NT but decreased (<0.5 MoM) PAPP-A and fβ-hCG odds ratios for VSD and HLHS were 19.5 and 25.6, respectively. Conclusions: Maternal serum biochemistry improves the detection of CHDs compared to NT measurement only. In cases with normal NT measurement but low concentrations of both PAPP-A and fβ-hCG, an alert for possible CHD, especially VSD, could be given with thorough examination of fetal heart in later ultrasound scans.
Keywords: chorionic gonadotropin beta subunit; pregnancy associated plasma protein A; adult; article; case control study; congenital heart malformation; controlled study; Down syndrome; embryo; Fallot tetralogy; female; fetus; fetus echography; fetus heart; Finland; first trimester pregnancy; heart ventricle septum defect; human; hypoplastic left heart syndrome; live birth; major clinical study; maternal serum; newborn; nuchal translucency measurement; pregnancy outcome; prenatal screening; priority journal; prospective study; receiver operating characteristic; stillbirth

Adverse Perioperative Events in Children with Complex Congenital Heart Disease Undergoing Operative Scoliosis Repair in the Contemporary Era - Przybylski, R.; Hedequist, D.J.; Nasr, V.G.; McCann, M.E.; Brustowicz, R.M.; Emans, J.B.; Marshall, A.C.; Brown, D.W. (Pediatric Cardiology, 2019)
Scoliosis is common in children with congenital heart disease (CHD) and may have deleterious effects on quality of life and hemodynamics. Relatively little is known about the outcomes of spinal fusion for scoliosis repair in children with complex CHD. We reviewed all cases of children with CHD undergoing first time spinal fusion excluding those with minor CHD between 1995 and 2015. Seventy-eight patients were identified and included in the study. 97.4% of patients included had undergone prior cardiac surgery and sixteen patients had single ventricle circulations. 17.9% of patients experienced a significant perioperative event defined as an aggregate of the presence of any of the following: need for early unanticipated reoperation, neurologic deficit, postoperative bleeding requiring intervention, end organ dysfunction, or death. There were no deaths in our cohort. 38.5% of patients experienced any adverse event, the majority of which were related to perioperative fluid shifts. Larger preoperative Cobb angle and longer length of spinal fusion were associated with increased risk of significant perioperative event while larger preoperative Cobb angle and longer length of spinal fusion, older age at time of surgery, single ventricle circulation, cyanosis and patients taking cardiac medications at the time of surgery were more likely to experience any adverse event. Operative repair of scoliosis in children with complex CHD has been performed without mortality over a 20-year period in a single institution, albeit with a higher rate of perioperative complication than is seen in the general pediatric population. Patients with large preoperative Cobb angles and cyanotic single ventricle circulations appear to be at the highest risk for perioperative complications.
Keywords: acute kidney tubule necrosis; adolescent; age; article; bacterial infection; cellulitis; child; circulation; Cobb angle; cohort analysis; congenital heart disease; cyanosis; delirium; device removal; disease association; drug eruption; drug use; female; fluid shift; group B streptococcal infection; heart surgery; heart ventricle tachycardia; high risk patient; Horner syndrome; human; hypervolemia; length of stay; lower extremity numbness; lower extremity weakness; major clinical study; male; meralgia paresthetica; motor evoked potential; neurologic disease; operative blood loss; paresthesia; peroperative complication; pneumonia; postoperative complication; postoperative hemorrhage; Propionibacterium acnes infection; reoperation; retrospective study; risk factor; scoliosis; septic shock; single ventricle circulation; somatosensory evoked potential; spinal cord infarction; spine fusion; spine surgery; stomach perforation; supraventricular tachycardia; thrombocytopenia; urinary tract infection; weakness; wound infection

Knowledge of Life-Long Cardiac Care by Adolescents and Young Adults with Congenital Heart Disease - Fernandes, S.M.; Verstappen, A.; Clair, M.; Rummell, M.; Barber, D.; Ackerman, K.; Dummer, K.; Mares, J.C.; Cannobio, M.M.; Reardon, L.C.; Long, J.; Crumb, S.; et al. (Pediatric Cardiology, 2019)
National management guidelines recommend that patients with moderate and complex congenital heart disease (CHD) receive life-long cardiac care (LLCC), guided in adulthood by an adult congenital heart disease (ACHD) specialist. However, the percentage of adult CHD patients who receive such care is quite low. Inadequate knowledge regarding LLCC may contribute to care interruption. We, therefore, sought to determine the knowledge of adolescents and young adults regarding LLCC. In this multi-center study, we administered a survey to patients 13–20 years of age with surgically repaired congenital heart disease. We assessed the understanding of both their need for LLCC and awareness of the type of recommended care providers. A total of 290/302 (96%) patients approached in the outpatient clinic setting (10 centers) agreed to study participation; mean age was 16.3 ± 2.3 years; patients were 62% male. While the need for LLCC was recognized by 78% of subjects, only 37% understood that an ACHD specialist in adulthood should guide this care. Only 37% of respondents stated that their current cardiology team had spoken to them about LLCC, but 90% wished to learn more. A substantial number of adolescents and young adults with moderate and complex CHD lack adequate knowledge about LLCC, but most have a desire to learn more about the type of care they will require in adulthood. Transition education/assessment ensuring successful transfer to adult-oriented care for this population should emphasize the importance of LLCC.
Keywords: adolescent; adult; aortic coarctation; arterial switch operation; article; attitude to illness; awareness; cardiologist; Caucasian; congenital heart disease; controlled study; cross-sectional study; descriptive research; Fallot tetralogy; female; Fontan procedure; general adult cardiologist; general practitioner; great vessels transposition; heart surgery; Hispanic; human; major clinical study; male; multicenter study; pediatric cardiologist; sex difference; terminal care; young adult

The ethics of lethal congenital malformations. Is palliative therapy possible? - Abdelbasit, O.; Seidahmed, M.; Alhussein, K.; Miqdad, A.; Mohsen, A.; Khalil, M.; Al-Mardawi, E.; Bahyan, R. (Journal of Clinical Neonatology, 2019)
Aim: This study aims to show that palliative care can be offered to babies born with lethal malformations according to the Islamic Code of Ethics, which takes into account the well-being of the mother and her fetus. Methods: For our study, a lethal congenital malformation is defined as a condition that invariably leads to death in utero or the newborn period regardless of attempted supportive care. The cases were identified during weekly prenatal meetings, which discuss abnormal fetal ultrasound findings and genetic testing to provide plans for their management. In addition, cases that were not diagnosed antenatally but diagnosed at birth were also included. The management plans for those cases with lethal malformations were discussed before birth, and the families were counseled, and their consent was taken for nonmonitoring of the fetus during pregnancy and noninterference with the newborn baby except for palliative care. Families who requested full support during pregnancy and delivery were given that option. Results: Over a period of 16 years from 2001 to 2016, a total number of 92705 babies were born in our hospital. Antenatal ultrasounds were performed by the feto-maternal physician team. There were 1563 abnormal fetal ultrasounds (1.7%) with significant various organs malformations. Of these abnormal ultrasounds, 384 were diagnosed as possible lethal congenital malformations (24.6%). The remaining abnormal fetal ultrasounds were compatible with life and were managed according to the standard clinical practices. Fetuses diagnosed with lethal malformations were discussed at length and parents were informed about the lethal outcome and the plan of nonmonitoring of the mother at delivery and avoidance of cesarean section except for maternal indication and eventual palliative care for the live newborn. Parents' consent was obtained, and the decision and the plan of the management are documented clearly in the mother's medical record file. With this management plan, we were able to offer palliative care to the cases of lethal congenital malformations who eventually expired within a short time. Conclusion: Within the guidance of the Islamic Jurisprudence (Figh), it is possible to manage cases of congenital malformations, which are considered incompatible with life palliatively and avoid unnecessary cesarean sections in the mother. This practice has resulted in better utilization of the beds in our busy neonatal intensive care unit.
Keywords: anencephalus; article; bone dysplasia; cesarean section; chondrodysplasia; chromosome aberration; congenital diaphragm hernia; congenital hydrocephalus; congenital malformation; disease severity; family counseling; family history; female; fetus echography; fetus hydrops; genetic screening; hemophagocytic syndrome; human; hydramnios; hypoplastic left heart syndrome; inborn error of metabolism; kidney agenesis; kidney polycystic disease; lactic acidemia; lethality; live birth; lung hypoplasia; major clinical study; Meckel syndrome; medical ethics; neonatal intensive care unit; newborn; newborn care; newborn death; newborn period; observational study; oligohydramnios; overall survival; palliative therapy; parental consent; pregnancy; prenatal period; priority journal; prospective study; survival time; thanatophoric dwarfism; trisomy 13; trisomy 18; trisomy 7; Walker Warburg syndrome

Low and decreased prevalence of congenital abdominal wall defect in Taiwan - Chen, M.-C.; Chen, J.-H.; Chen, Y.; Tsai, Y.-H.; Lee, C.-H. (Journal of Pediatric Surgery, 2019)
Purpose: This study aims to identify the prevalence of Congenital abdominal wall defects (AWD), hospital outcomes, and related congenital abnormalities in Taiwan by using the National Health Insurance Research Database (NHIRD). Materials and methods: From 1998 through 2013, all pediatric patients with AWD were collected via ICD-9-CM diagnostic code 756.7x (“congenital anomalies of abdominal wall”) or procedure codes (54.71, 54.72 for Gastroschisis repair (GS-repair); 54.63, 53.41, 53.49 for other abdominal wall repair (O-AWD)) recoded in NHIRD. We used public national birth data for calculating the prevalence. We used CDC/BPA coding rubrics to identify accompanying congenital abnormalities. Results: A total 594 babies with AWD, including 179 patients in GS-repair group and 326 patients in O-AWD-repair group, are identified with 113.5 months median followed-up. The overall prevalence for AWD was 1.65 in 10,000 births and decreased over time. The prevalences of GS-repaired and O-AWD-repaired are 0.50 and 0.90 in 10,000 births. The 1-year-mortality rates of GS-repair and O-AWD-repair are 6.15% and 7.23%. 24.58% GS-repair patients and 30.06% O-AWD-repair patients have congenital abnormalities. 8.38% GS-repair patients and 6.44% O-AWD-repair patients received the following groin hernia-repair procedures. Conclusion: Our results showed that the prevalence of AWD was low and decreased over time in Taiwan. Level of evidence: Level II: Prognosis Study, Retrospective study.
Keywords: abdominal wall defect; anotia; anus atresia; aortic coarctation; aortic valve stenosis; article; bile duct atresia; bladder exstrophy; cleft lip with or without cleft palate; congenital cataract; congenital hip dislocation; diaphragm hernia; Down syndrome; encephalocele; endocardial cushion defect; epispadias; esophagus atresia; esophagus stenosis; Fallot tetralogy; female; follow up; gastroschisis; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; Hirschsprung disease; human; hypospadias; ICD-9-CM; intestine atresia; kidney agenesis; major clinical study; male; microtia; mortality rate; national health insurance; newborn; obstructive genitourinary defect; patent ductus arteriosus; pediatric patient; prevalence; priority journal; pulmonary valve atresia; pulmonary valve stenosis; pylorus stenosis; renal dysgenesis; spinal dysraphism; Taiwan; tracheoesophageal fistula; tricuspid valve atresia; tricuspid valve stenosis; trisomy 13; trisomy 18; urogenital tract disease

Transition Readiness in Adolescents and Young Adults with Heart Disease: Can We Improve Quality of Life? - Uzark, K.; Afton, K.; Yu, S.; Lowery, R.; Smith, C.; Norris, M.D. (Journal of Pediatrics, 2019)
Objectives: We previously reported common knowledge deficits and lack of transition readiness in 13- 25-year-olds with congenital or acquired heart disease. The aims of this study were to re-evaluate transition readiness in this cohort at follow-up and to examine the relationship between changes in transition readiness and quality of life (QOL). Study design: In this prospective cohort study, patients completed the Transition Readiness Assessment and the Pediatric Quality of Life Inventory using an e-tablet, web-based format at a routine follow-up visit. Changes from initial to follow-up scores were evaluated. Results: Sixty-five percent of patients (106 of 164) completed follow-up assessments at a median age of 18.7 years (IQR, 16.5-21.2 years) at a median follow-up of 1 year. The average perceived knowledge deficit score (percent of items with no knowledge) at follow-up was 18.0 ± 15.2%, which decreased from 24.7 ± 16.5% (P < .0001). On a 100-point scale, the mean score for self-efficacy increased from 71.4 ± 17.0 to 76.7 ± 18.2 (P = .0004) and for self-management increased from 47.9 ± 18.4 to 52.0 ± 20.7 (P = .004). Although physical QOL did not change, the mean psychosocial QOL score increased significantly (P = .02). A decrease in the knowledge deficit score at follow-up was significantly associated with an increased psychosocial QOL score (P = .03). An increase in the self-efficacy score was associated with an increase in psychosocial QOL score (P = .04), especially social QOL (P = .02). Conclusions: Although deficits in knowledge and self-management skills persist, transition readiness assessment and recognition of deficits can improve transition readiness with improved psychosocial QOL.
Keywords: adolescent; adult; article; cohort analysis; disease severity; female; follow up; heart disease; heart single ventricle; human; knowledge; male; Pediatric Quality of Life Inventory; priority journal; prospective study; quality of life; self care; self concept; social psychology; young adult

Hand-held echocardiography in children with hypoplastic left heart syndrome - Riley, A.F.; Ocampo, E.C.; Hagan, J.; Lantin-Hermoso, M.R. (Congenital Heart Disease, 2019)
Background: When performed by cardiologists, hand-held echocardiography (HHE) can assess ventricular systolic function and valve disease in adults, but its accuracy and utility in congenital heart disease is unknown. In hypoplastic left heart syndrome (HLHS), the echocardiographic detection of depressed right ventricular (RV) systolic function and higher grade tricuspid regurgitation (TR) can identify patients who are at increased risk of morbidity and mortality and who may benefit from additional imaging or medical therapies. Methods: Children with HLHS after Stage I or II surgical palliation (Norwood or Glenn procedures) were prospectively enrolled. Subjects underwent HHE by a pediatric cardiologist on the same day as standard echocardiography (SE). Using 4-point scales, bedside HHE assessment of RV systolic function and TR were compared with blinded assessment of offline SE images. Concordance correlation coefficient (CCC) was used to evaluate agreement. Results: Thirty-two HHEs were performed on 15 subjects (Stage I: n = 17 and Stage II: n = 15). Median subject age was 3.4 months (14 days-4.2 years). Median weight was 5.9 kg (2.6-15.4 kg). Bedside HHE assessment of RV systolic function and TR severity had substantial agreement with SE (CCC = 0.80, CCC = 0.74, respectively; P <.001). HHE sensitivity and specificity for any grade of depressed RV systolic function were 100% and 92%, respectively, and were 94% and 88% for moderate or greater TR, respectively. Average HHE scan time was 238 seconds. Conclusions: HHE offers a rapid, bedside tool for pediatric cardiologists to detect RV systolic dysfunction and hemodynamically significant TR in HLHS.
Keywords: echocardiograph; portable ultrasound scanner; age distribution; article; body weight; cardiac imaging; cardiologist; child; clinical article; controlled study; correlation coefficient; diagnostic accuracy; diagnostic test accuracy study; disease severity; echocardiography; female; Glenn shunt; heart right ventricle function; human; hypoplastic left heart syndrome; infant; male; morbidity; mortality; newborn; Norwood procedure; pediatrician; pilot study; priority journal; prospective study; risk factor; sensitivity and specificity; single blind procedure; systolic dysfunction; tricuspid valve regurgitation; Vscan

Cognitive Function in Pediatric Hypoplastic Left Heart Syndrome: Systematic Review and Meta-Analysis - Siciliano, R.E.; Prussien, K.V.; Lee, C.A.; Patel, N.J.; Murphy, L.K.; Compas, B.E.; Jordan, L.C. (Journal of pediatric psychology, 2019)
OBJECTIVE: Despite surgical palliation, children with hypoplastic left heart syndrome (HLHS) have compromised cardiac functioning and increased risk for cognitive deficits. We quantitatively reviewed the empirical data from this literature. METHODS: The present meta-analysis included 13 studies reporting cognitive function for children with HLHS between the ages of 2 years and 6 months and 17 years that used standardized assessments of Full Scale IQ (FSIQ), Verbal IQ (VIQ), and Performance IQ (PIQ). Differences in cognitive function were assessed relative to normative data, and we examined sample mean age and publication year as moderators. RESULTS: Large effects were found for FSIQ (g = -.87, 95% CI [-1.10, -.65], M = 86.88) and PIQ (g = -.89, 95% CI [-1.11, -.68], M = 86.56), and a medium effect was found for VIQ (g = -.61, 95% CI [-.84, -.38], M = 90.82). All models demonstrated significant heterogeneity. Meta-regression analyses of effect size via Hedges' g on child age revealed a significant effect on FSIQ (coefficient = -.07, 95% CI [-.12, -.01], p < .01, R2 = .40) indicating a loss of 1.1 FSIQ points across studies with each increased year of mean sample age. CONCLUSIONS: Deficits in FSIQ may reflect chronic brain injury or failure to make expected gains as children age. This review highlights the importance of early intervention in this population, and the need for longitudinal studies analyzing more specific domains of cognitive function and potential moderators.
Keywords: adolescent; child; cognitive defect; complication; human; hypoplastic left heart syndrome; meta analysis; pathophysiology; preschool child

Indian guidelines for indications and timing of intervention for common congenital heart diseases: Revised and updated consensus statement of the Working group on management of congenital heart diseases - Saxena, A.; Relan, J.; Agarwal, R.; Awasthy, N.; Azad, S.; Chakrabarty, M.; Dagar, K.; Devagourou, V.; Dharan, B.; Gupta, S.; Iyer, K.; Jayranganath, M.; et al. (Annals of Pediatric Cardiology, 2019)
A number of guidelines are available for the management of congenital heart diseases (CHD) from infancy to adult life. However, these guidelines are for patients living in high-income countries. Separate guidelines, applicable to Indian children, are required when recommending an intervention for CHD, as often these patients present late in the course of the disease and may have coexisting morbidities and malnutrition. Guidelines emerged following expert deliberations at the National Consensus Meeting on Management of Congenital Heart Diseases in India, held on August 10 and 11, 2018, at the All India Institute of Medical Sciences. The meeting was supported by Children's HeartLink, a nongovernmental organization based in Minnesota, USA. The aim of the study was to frame evidence-based guidelines for (i) indications and optimal timing of intervention in common CHD; (ii) follow-up protocols for patients who have undergone cardiac surgery/catheter interventions for CHD; and (iii) indications for use of pacemakers in children. Evidence-based recommendations are provided for indications and timing of intervention in common CHD, including left-to-right shunts (atrial septal defect, ventricular septal defect, atrioventricular septal defect, patent ductus arteriosus, and others), obstructive lesions (pulmonary stenosis, aortic stenosis, and coarctation of aorta), and cyanotic CHD (tetralogy of Fallot, transposition of great arteries, univentricular hearts, total anomalous pulmonary venous connection, Ebstein's anomaly, and others). In addition, protocols for follow-up of postsurgical patients are also described, disease wise. Guidelines are also given on indications for implantation of permanent pacemakers in children.
Keywords: aortic stent; artificial heart pacemaker; atrial septal occluder; echocardiograph; endocardial pacemaker electrode; epicardial pacemaker; vascular stent; acetylsalicylic acid; anticoagulant therapy; antiplatelet activity; aortic coarctation; aortic regurgitation; aortic stenosis; aortopulmonary septal defect; article; atrioventricular septal defect; balloon dilatation; clinical assessment; congenital heart disease; consensus development; cyanosis; Down syndrome; Ebstein anomaly; echocardiography; electrocardiogram; Fallot tetralogy; follow up; great vessels transposition; heart atrium enlargement; heart atrium septum defect; heart catheterization; heart electrophysiology; heart right ventricle double outlet; heart right ventricle function; heart single ventricle; heart valve replacement; heart ventricle septum defect; human; lung artery pressure; lung vein drainage anomaly; mitral valve regurgitation; mouth hygiene; pacemaker implantation; patent ductus arteriosus; practice guideline; prematurity; pulmonary hypertension; pulmonary valve atresia; pulmonary valve replacement; pulmonary valve stenosis; pulmonary vascular obstructive disease; thorax radiography; transesophageal echocardiography; transthoracic echocardiography

What are the important morbidities associated with paediatric cardiac surgery? A mixed methods study - Brown, K.L.; Pagel, C.; Ridout, D.; Wray, J.; Anderson, D.; Barron, D.J.; Cassidy, J.; Davis, P.; Hudson, E.; Jones, A.; McLean, A.; Morris, S.; et al. (BMJ Open, 2019)
Given the current excellent early mortality rates for paediatric cardiac surgery, stakeholders believe that this important safety outcome should be supplemented by a wider range of measures. Our objectives were to prospectively measure the incidence of morbidities following paediatric cardiac surgery and to evaluate their clinical and health-economic impact over 6 months. Design The design was a prospective, multicentre, multidisciplinary mixed methods study. Setting The setting was 5 of the 10 paediatric cardiac surgery centres in the UK with 21 months recruitment. Participants Included were 3090 paediatric cardiac surgeries, of which 666 patients were recruited to an impact substudy. Results Families and clinicians prioritised: Acute neurological event, unplanned re-intervention, feeding problems, renal replacement therapy, major adverse events, extracorporeal life support, necrotising enterocolitis, postsurgical infection and prolonged pleural effusion or chylothorax. Among 3090 consecutive surgeries, there were 675 (21.8%) with at least one of these morbidities. Independent risk factors for morbidity included neonatal age, complex heart disease and prolonged cardiopulmonary bypass (p<0.001). Among patients with morbidity, 6-month survival was 88.2% (95% CI 85.4 to 90.6) compared with 99.3% (95% CI 98.9 to 99.6) with none of the morbidities (p<0.001). The impact substudy in 340 children with morbidity and 326 control children with no morbidity indicated that morbidity-related impairment in quality of life improved between 6 weeks and 6 months. When compared with children with no morbidities, those with morbidity experienced a median of 13 (95% CI 10.2 to 15.8, p<0.001) fewer days at home by 6 months, and an adjusted incremental cost of £21 292 (95% CI £17 694 to £32 423, p<0.001). Conclusions Evaluation of postoperative morbidity is more complicated than measuring early mortality. However, tracking morbidity after paediatric cardiac surgery over 6 months offers stakeholders important data that are of value to parents and will be useful in driving future quality improvement.
Keywords: age; aortic arch anomaly; aortic occlusion; aortic regurgitation; article; cardiopulmonary bypass; child; chylothorax; controlled study; extracorporeal oxygenation; feeding difficulty; female; great vessels transposition; health care cost; heart atrium septum defect; heart single ventricle; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; incidence; infant; lung vein drainage anomaly; major clinical study; male; morbidity; necrotizing enterocolitis; newborn; patent ductus arteriosus; pediatric surgery; pleura effusion; postoperative complication; preschool child; prospective study; pulmonary valve atresia; quality of life; renal replacement therapy; surgical infection; survival rate; survival time; tricuspid valve disease

A Quality Bundle to Support High-Risk Pediatric Ventricular Assist Device Implantation - Knoll, C.; Chen, S.; Murray, J.M.; Dykes, J.C.; Yarlagadda, V.V.; Rosenthal, D.N.; Almond, C.S.; Maeda, K.; Shin, A.Y. (Pediatric Cardiology, 2019)
Pediatric ventricular assist device (VAD) implantation outcomes are increasingly promising for children with dilated cardiomyopathy and advanced decompensated heart failure (ADHF). VAD placement in patients with clinical features such as complex congenital cardiac anatomy, small body size, or major comorbidities remains problematic. These comorbidities have been traditionally prohibitive for VAD consideration leaving these children as a treatment-orphaned population. Here we describe the quality bundle surrounding these patients with ADHF considered high risk for VAD implantation at our institution. Over a 7-year period, a quality bundle aimed at the peri-operative care for children with high-risk features undergoing VAD implantation was incrementally implemented at a tertiary children’s hospital. Patients were considered high risk if they were neonates (< 30 days), had single-ventricle physiology, non-dilated cardiomyopathy, biventricular dysfunction, or significant comorbidities. The quality improvement bundle evolved to include (1) structured team-based peri-operative evaluation, (2) weekly VAD rounds addressing post-operative device performance, (3) standardized anticoagulation strategies, and (4) a multidisciplinary system for management challenges. These measures aimed to improve communication, standardize management, allow for ongoing process improvement, and incorporate principles of a high-reliability organization. Between January 2010 and December 2017, 98 patients underwent VAD implantation, 48 (49%) of which had high-risk comorbidities and a resultant cohort survival-to-transplant rate of 65%. We report on the evolution of a quality improvement program to expand the scope of VAD implantation to patients with high-risk clinical profiles. This quality bundle can serve as a template for future large-scale collaborations to improve outcomes in these treatment-orphaned subgroups.
Keywords: ventricular assist device; anticoagulant agent; adolescent; adult; advanced decompensated heart failure; anticoagulant therapy; article; child; cohort analysis; comorbidity; congestive cardiomyopathy; controlled study; female; health care quality; heart failure; heart single ventricle; heart ventricle failure; high risk patient; human; implantation; infant; interpersonal communication; major clinical study; male; newborn; observational study; patient assessment; pediatric hospital; perioperative period; preschool child; reliability; retrospective study; risk assessment; school child; standardization; survival time; tertiary care center

Utility of 3D Printed Cardiac Models for Medical Student Education in Congenital Heart Disease: Across a Spectrum of Disease Severity - Smerling, J.; Marboe, C.C.; Lefkowitch, J.H.; Pavlicova, M.; Bacha, E.; Einstein, A.J.; Naka, Y.; Glickstein, J.; Farooqi, K.M. (Pediatric Cardiology, 2019)
The most common modes of medical education for congenital heart disease (CHD) rely heavily on 2-dimensional imaging. Three-dimensional (3D) printing technology allows for the creation of physical cardiac models that can be used for teaching trainees. 3D printed cardiac models were created for the following lesions: pulmonic stenosis, atrial septal defect, tetralogy of Fallot, d-transposition of the great arteries, coarctation of the aorta, and hypoplastic left heart syndrome. Medical students participated in a workshop consisting of different teaching stations. At the 3D printed station, students completed a pre- and post-intervention survey assessing their knowledge of each cardiac lesion on a Likert scale. Students were asked to rank the educational benefit of each modality. Linear regression was utilized to assess the correlation of the mean increase in knowledge with increasing complexity of CHD based on the Aristotle Basic Complexity Level. 45 medical students attended the CHD workshop. Students’ knowledge significantly improved for every lesion (p < 0.001). A strong positive correlation was found between mean increase in knowledge and increasing complexity of CHD (R2 = 0.73, p < 0.05). The 3D printed models, pathology specimens and spoken explanation were found to be the most helpful modalities. Students “strongly agreed” the 3D printed models made them more confident in explaining congenital cardiac anatomy to others (mean = 4.23, ± 0.69), and that they recommend the use of 3D models for future educational sessions (mean = 4.40, ± 0.69). 3D printed cardiac models should be included in medical student education particularly for lesions that require a complex understanding of spatial relationships.
Keywords: adult; aortic coarctation; article; attitude to health; biological model; congenital heart disease; disease severity; equipment and supplies utilization; Fallot tetralogy; female; great vessels transposition; heart atrium septum defect; human; hypoplastic left heart syndrome; male; medical education; medical student; pulmonary valve stenosis; spatial analysis; teaching; three dimensional printing; two dimensional echocardiography; workshop; young adult

Refining The Society of Thoracic Surgeons Congenital Heart Surgery Database Mortality Risk Model With Enhanced Risk Adjustment for Chromosomal Abnormalities, Syndromes, and Noncardiac Congenital Anatomic Abnormalities - Jacobs, J.P.; O'Brien, S.M.; Hill, K.D.; Kumar, S.R.; Austin, E.H.; Gaynor, J.W.; Gruber, P.J.; Jonas, R.A.; Pasquali, S.K.; Pizarro, C.; St. Louis, J.D.; Meza, J.; et al. (Annals of Thoracic Surgery, 2019)
Background: The Society of Thoracic Surgeons Congenital Heart Surgery Database Mortality Risk Model adjusts not only for procedure and age group pairings but also for additional patient factors, including the binary presence or absence of a chromosomal abnormality (CA), syndrome (S), and/or a noncardiac congenital anatomic abnormality (NCAA). This analysis refines case-mix adjustment by adding more granular adjustment for individual conditions (CA, S, and NCAA), consistent with a hypothesis that associated risk of mortality differs between individual conditions. Methods: CA/S corresponding to the same condition were merged to a single condition code. Odds ratios were estimated for all CA/S. For CA/S associated with at least 10 deaths in neonates and infants and at least 10 deaths in children and adults, odds ratios were estimated for the effect of the CA/S separately in neonates/infants and in children/adults. In addition to these condition/age interactions, condition/age/procedure interactions were explored (eg, effect of Down syndrome was estimated based on age and procedure subgroups, including atrioventricular canal repair and single-ventricle palliation). Bayesian modeling was used to create 5 maximally homogeneous groups of CA/S from 81 candidate CA/S variables. A standard logistic regression model then incorporated indicator variables for the 5 categories of CAs/Ss, 7 unique NCAAs, and all other covariates in the previously published Society of Thoracic Surgeons Congenital Heart Surgery Database Mortality Model. Results: Analysis included 107,062 operations in 100 centers (2010 to 2015). Operative Mortality was 3,629 (3.4%). In the development sample, the C statistics of the original nonaugmented model and the augmented model were 0.872 and 0.875, respectively. Conclusions: The Society of Thoracic Surgeons Congenital Heart Surgery Database Mortality Risk Model has been augmented by addition of covariates representing individual CAs, Ss, and NCAAs.
Keywords: acrocephalosyndactyly; adult; age; Alagille syndrome; article; Bayes theorem; cat cry syndrome; child; chromosome aberration; congenital disorder; congenital rubella syndrome; Costello syndrome; de Lange syndrome; DiGeorge syndrome; Down syndrome; Edwards syndrome; Ellis van Creveld syndrome; fetal alcohol syndrome; Goldenhar syndrome; heart surgery; heterotaxy syndrome; Holt Oram syndrome; human; Hunter syndrome; infant; Jacobsen syndrome; Kabuki makeup syndrome; Kartagener syndrome; Klinefelter syndrome; Loeys Dietz syndrome; long QT syndrome; major clinical study; medical society; monosomy X; mortality risk; newborn; Noonan syndrome; omphalocele; priority journal; Rubinstein syndrome; short QT syndrome; situs inversus; Smith Lemli Opitz syndrome; surgical mortality; syndrome; trisomy; trisomy 13; Turner syndrome; Williams Beuren syndrome; Wolf Hirschhorn syndrome; Wolff Parkinson White syndrome

Relationship of Aortic Stiffness to Exercise and Ventricular Volumes in Single Ventricles - Biko, D.M.; Gaynor, J.W.; Partington, S.L.; Harris, M.A.; Whitehead, K.K.; Trusty, P.; Yoganathan, A.P.; Fogel, M.A. (Annals of Thoracic Surgery, 2019)
Background: Patients with single ventricle (SV) may often undergo aortic reconstruction that creates a stiff large vessel, increasing afterload and affecting exercise performance. The objective of this study was to determine the relationship of pulse wave velocity (PWV) and distensibility in reconstructed and normal aortic arches after Fontan with exercise variables. Methods: PWV and distensibility of the descending aorta at the level of the diaphragm (DAo) were calculated with real-time exercise cardiac magnetic resonance in 48 patients with SV after Fontan (18 after aortic reconstruction; 30 without aortic reconstruction) and compared with metabolic exercise stress test variables. Results: PWV was greater in the reconstructed group than in the non-reconstructed group (median 4.4 m/s [range: 2.3 to 9.8 m/s] versus 3.6 [range: 2.6 to 6.3 m/s], respectively, p = 0.003). Statistically significant inverse correlations were found between PWV and end-diastolic, end-systolic, and stroke volumes at rest and at exercise in the reconstructed group. In addition, inverse correlations also existed in the reconstructed group between distensibility of the DAo and the exercise variables such as peak oxygen pulse (R = 0.56, p = 0.02), peak oxygen consumption (R = 0.63, p = 0.008), oxygen consumption at ventilatory anaerobic threshold (R = 0.48, p = 0.04), and peak work (R = 0.54, p = 0.02). Similar correlations were not seen in patients with non-reconstructed aortas. Conclusions: Patients with SV with reconstructed aortas have increased aortic stiffness, increasing afterload on the ventricle. Native DAo stiffness distal to the reconstruction is inversely correlated with exercise performance, presumably to decrease impedance mismatch to maintain homogeneity of the aortic wall. This information suggests a possible mechanism for decreased exercise performance in patients with SV with aortic reconstructions.
Keywords: adolescent; adult; anaerobic threshold; aortic arch; aortic reconstruction; arterial stiffness; article; cardiac imaging; cardiovascular magnetic resonance; child; clinical article; descending aorta; diaphragm; end diastolic volume; end systolic volume; exercise; exercise test; female; Fontan procedure; heart single ventricle; heart stroke volume; heart volume; human; male; oxygen consumption; priority journal; pulse wave; pulse wave distensibility

Maternal voluntary exercise mitigates oxidative stress and incidence of congenital heart defects in pre-gestational diabetes - Saiyin, T.; Engineer, A.; Greco, E.R.; Kim, M.Y.; Lu, X.; Jones, D.L.; Feng, Q. (Journal of Cellular and Molecular Medicine, 2019)
Women with pre-gestational diabetes have a higher risk of producing children with congenital heart defects (CHDs), caused predominantly by hyperglycemia-induced oxidative stress. In this study, we evaluated if exercise during pregnancy could mitigate oxidative stress and reduce the incidence of CHDs in the offspring of diabetic mice. Female mice were treated with streptozotocin to induce pre-gestational diabetes, then mated with healthy males to produce offspring. They were also given access to running wheels 1 week before mating and allowed to exercise voluntarily until E18.5. Heart morphology, gene expression, and oxidative stress were assessed in foetal hearts. Maternal voluntary exercise results in a significantly lower incidence of CHDs from 59.5% to 25%. Additionally, diabetes-induced defects in coronary artery and capillary morphogenesis were also lower with exercise. Myocardial cell proliferation and epithelial-mesenchymal transition at E12.5 was significantly lower with pre-gestational diabetes which was mitigated with maternal exercise. Cardiac gene expression of Notch1, Snail1, Gata4 and Cyclin D1 was significantly higher in the embryos of diabetic mice that exercised compared to the non-exercised group. Furthermore, maternal exercise produced lower reactive oxygen species (ROS) and oxidative stress in the foetal heart. In conclusion, maternal exercise mitigates ROS and oxidative damage in the foetal heart, and results in a lower incidence of CHDs in the offspring of pre-gestational diabetes. Exercise may be an effective intervention to compliment clinical management and further minimize CHD risk in mothers with diabetes.
Keywords: bone morphogenetic protein; cyclin D1; endothelial nitric oxide synthase; glucose; hypoxia inducible factor 1alpha; Notch1 receptor; reactive oxygen metabolite; RNA 28S; superoxide dismutase; transcription factor GATA 4; transcription factor Snail; animal experiment; animal model; animal tissue; article; atrioventricular septal defect; autism; cell proliferation; congenital blood vessel malformation; congenital heart malformation; controlled study; densitometry; embryo; epithelial mesenchymal transition; exercise; exercise intensity; female; fetus; gene expression; glucose intake; heart right ventricle double outlet; heart ventricle septum defect; histology; hypoplastic left heart syndrome; image reconstruction; lipid peroxidation; male; mouse; nonhuman; oxidative stress; pregnancy; pregnancy diabetes mellitus; pregnancy outcome; priority journal; progeny; protein expression; real time polymerase chain reaction; reverse transcription polymerase chain reaction; streptozotocin-induced diabetes mellitus; three-dimensional imaging; upregulation; Western blotting

Stress increases intracardiac 4D flow cardiovascular magnetic resonance -derived energetics and vorticity and relates to VO2max in Fontan patients - Kamphuis, V.P.; Elbaz, M.S.M.; van den Boogaard, P.J.; Kroft, L.J.M.; Lamb, H.J.; Hazekamp, M.G.; Jongbloed, M.R.M.; Blom, N.A.; Helbing, W.A.; Roest, A.A.W.; Westenberg, J.J.M. (Journal of cardiovascular magnetic resonance : official journal of the Society for Cardiovascular Magnetic Resonance, 2019)
BACKGROUND: We hypothesize that dobutamine-induced stress impacts intracardiac hemodynamic parameters and that this may be linked to decreased exercise capacity in Fontan patients. Therefore, the purpose of this study was to assess the effect of pharmacologic stress on intraventricular kinetic energy (KE), viscous energy loss (EL) and vorticity from four-dimensional (4D) Flow cardiovascular magnetic resonance (CMR) imaging in Fontan patients and to study the association between stress response and exercise capacity. METHODS: Ten Fontan patients underwent whole-heart 4D flow CMR before and during 7.5 μg/kg/min dobutamine infusion and cardiopulmonary exercise testing (CPET) on the same day. Average ventricular KE, EL and vorticity were computed over systole, diastole and the total cardiac cycle (vorticity_volavg cycle, KEavg cycle, ELavg cycle). The relation to maximum oxygen uptake (VO2 max) from CPET was tested by Pearson's correlation or Spearman's rank correlation in case of non-normality of the data. RESULTS: Dobutamine stress caused a significant 88 ± 52% increase in KE (KEavg cycle: 1.8 ± 0.5 vs 3.3 ± 0.9 mJ, P < 0.001), a significant 108 ± 49% increase in EL (ELavg cycle: 0.9 ± 0.4 vs 1.9 ± 0.9 mW, P < 0.001) and a significant 27 ± 19% increase in vorticity (vorticity_volavg cycle: 3441 ± 899 vs 4394 ± 1322 mL/s, P = 0.002). All rest-stress differences (%) were negatively correlated to VO2 max (KEavg cycle: r = - 0.83, P = 0.003; ELavg cycle: r = - 0.80, P = 0.006; vorticity_volavg cycle: r = - 0.64, P = 0.047). CONCLUSIONS: 4D flow CMR-derived intraventricular kinetic energy, viscous energy loss and vorticity in Fontan patients increase during pharmacologic stress and show a negative correlation with exercise capacity measured by VO2 max.
Keywords: beta 1 adrenergic receptor stimulating agent; dobutamine; adolescent; cine magnetic resonance imaging; comparative study; computer assisted diagnosis; congenital heart malformation; coronary artery blood flow; diagnostic imaging; drug effect; exercise test; exercise tolerance; female; Fontan procedure; hemodynamics; human; male; myocardial perfusion imaging; oxygen consumption; pathophysiology; predictive value; procedures; prospective study; time factor; treatment outcome; young adult

The first Fetal Echocardiography experience for Prenatal diagnosis of Congenital Heart Disease in Lebanon: Successes and challenges - Charafeddine, F.; Hachem, A.; Kibbi, N.; Abutaqa, M.; Bitar, F.; Bulbul, Z.; El-Rassi, I.; Arabi, M. (Journal of the Saudi Heart Association, 2019)
Objectives: To describe the first Lebanese fetal echocardiography experience for prenatal diagnosis of congenital heart diseases (CHD), showcase successes, and hurdles. Methods: This was a retrospective study from January 2014 to December 2017. A total of 350 fetal echocardiograms for 299 fetuses were performed at the Children's Heart Center at the American University of Beirut, the only fetal center in Lebanon. Data were collected regarding diagnosis, reasons for referral, and timing of referral. Results: The mean gestational age at presentation was 25.3 weeks (standard deviation 4.9 weeks). The primary reasons for referral were abnormal anomaly scan (81 27%), history of previous child with CHD (48 16%), and pre-existing maternal congenital heart disease (15 5%). A total of 144 fetal echocardiograms were normal and 155 patients were diagnosed prenatally with CHD giving a detection rate of 44%. The most identified cardiac lesions were ventricular septal defects (31, 20%), atrial septal defects (15, 9.7%). Significant CHD defined as major abnormalities which would impact pregnancy and future quality of life of the baby were identified in 78 fetuses, with a detection rate of 22%. Conclusion: High rates of detection are mainly due to low rates of referral when indicated and possibly parental anxiety regarding CHD diagnosis.
Keywords: arterial trunk; article; congenital heart disease; Ebstein anomaly; Fallot tetralogy; fetus; fetus electrocardiography; gestational age; great vessels transposition; heart atrium septum defect; heart center; heart left right shunt; heart outflow tract obstruction; heart right ventricle double outlet; heart ventricle septum defect; human; hypoplastic left heart syndrome; Lebanon; major clinical study; patient referral; prenatal diagnosis; priority journal; quality of life; retrospective study

Congenital heart diseases in consanguineous marriages in tikrit-Iraq - Abd, M.A.; Sulaiman, R.; Sarhat, A.R. (Indian Journal of Public Health Research and Development, 2019)
Consanguineous marriage means a union occur between related individuals as second cousins or closer. Iraq as part Middle Eastern States show a high rate of consanguineous marriage due to tribal society. In Iraq, consanguineous marriage is a socially supported custom. To study the association of consanguinity as a risk factor for congenital heart diseases (CHDs). Patients with suggestive signs of CHD admitted Tikrit teaching hospital were subject to diagnostic investigations. Case data includes: name, age, gender, and cause of admission. Parents data includes: age, residence, degree of consanguinity, and history of family recurrent CHDs. Congenital heart diseases was slightly higher in females than males, and there is 40% of studied cases were from positive consanguinity families. This study shows that the least congenital heart disease age reported was neonatal period, and the highest in ages between 1-5 years. Consanguinity in CHD was present in 81 cases (40%) and absent in 123 cases (60%). Family history in CHD was positive in (38%). most common congenital abnormality associated with CHD was Down’s syndrome.
Keywords: age; aortic stenosis; aortopulmonary septal defect; article; child; congenital heart disease; consanguineous marriage; cross-sectional study; Down syndrome; echocardiography; Edwards syndrome; family history; female; heart single ventricle; human; infant; Iraq; major clinical study; male; newborn; observational study; pulmonary valve atresia; questionnaire; risk factor; school child

Altered brain diffusion tensor imaging indices in adolescents with the Fontan palliation - Singh, S.; Roy, B.; Pike, N.; Daniel, E.; Ehlert, L.; Lewis, A.B.; Halnon, N.; Woo, M.A.; Kumar, R. (Neuroradiology, 2019)
Purpose: Single ventricle heart disease (SVHD) patients show injury in brain sites that regulate autonomic, mood, and cognitive functions. However, the nature (acute or chronic changes) and extent of brain injury in SVHD are unclear. Our aim was to examine regional brain tissue damage in SVHD over controls using DTI-based mean diffusivity (MD), axial diffusivity (AD), radial diffusivity (RD), and fractional anisotropy (FA) procedures. Methods: We collected two DTI series (3.0-T MRI), mood and cognitive data, from 27 SVHD and 35 control adolescents. Whole-brain MD, AD, RD, and FA maps were calculated from each series, realigned and averaged, normalized to a common space, smoothed, and compared between groups using ANCOVA (covariates, age and sex; false discovery rate, p < 0.05). Region-of-interest analyses were performed to calculate MD, AD, RD, and FA values for magnitude assessment between groups. Results: SVHD patients showed impaired mood and cognitive functions over healthy adolescents. Multiple brain sites in SVHD showed increased MD values, including the insula, caudate, cingulate, hypothalamus, thalamus, medial prefrontal and frontal cortices, parahippocampal gyrus, hippocampus, precentral gyrus, amygdala, cerebellum, corpus callosum, basal forebrain, mammillary bodies, internal capsule, midbrain, fornix, and occipital, parietal, and temporal cortices, indicating chronic tissue changes. Similar areas showed either increased AD or RD values, with RD changes more enhanced over AD in SVHD compared to controls. Few brain regions emerged with increased or decreased FA values in SVHD patients over controls. Conclusion: SVHD adolescents, more than a decade from their last surgical procedure, show widespread brain abnormalities in autonomic, mood, and cognitive regulatory areas. These findings indicate that brain injury is in a chronic stage in SVHD with predominantly myelin changes that may result from previous hypoxia/ischemia- or developmental-induced processes.
Keywords: adolescent; adult; amygdala; anterior cingulate; anterior insula; article; axial diffusivity; basal forebrain; brain fornix; brain region; brain tissue; capsula interna; caudate nucleus; cerebellar peduncle; cerebellum; cerebellum cortex; cingulate gyrus; cognition; controlled study; corpus callosum; diffusion tensor imaging; female; Fontan procedure; fractional anisotropy; frontal cortex; heart single ventricle; hippocampus; human; hypothalamus; major clinical study; male; mammillary body; mean diffusivity; medial prefrontal cortex; mesencephalon; mood; neuroimaging; occipital cortex; palliative therapy; parahippocampal gyrus; parietal cortex; posterior cingulate; posterior insula; prefrontal cortex; primary motor cortex; priority journal; radial diffusivity; temporal cortex; thalamus

Cost-Effectiveness of Percutaneous Lymphatic Embolization for Management of Plastic Bronchitis - Benjamin, J.L.; Rychik, J.; Johnstone, J.A.; Nadolski, G.J.; Itkin, M. (World Journal for Pediatric and Congenital Heart Surgery, 2019)
Background: Plastic bronchitis is a dreaded complication of single ventricle physiology occurring following palliation via Fontan procedure. Medical management of plastic bronchitis often fails, requiring heart transplantation. Percutaneous lymphatic embolization is an emerging treatment for plastic bronchitis. Methods: To determine the cost-effectiveness of competing management strategies, a modified Markov model was constructed with patients transiting through treatments—medical management, lymphatic embolization, or heart transplantation from a hospital system perspective. Health state transitions were modeled using an institutional review board–approved retrospective review of the Children’s Hospital of Pennsylvania’s plastic bronchitis cohort. Medication pricing data were obtained from the National Inpatient Sample. Differences in costs and quality-adjusted life years (QALYs) over a five-year horizon for each group were determined. The incremental cost-effectiveness ratio was then calculated. Results: The mean cost of lymphatic embolization from procedure performance was US$340,941, US$385,841 for heart transplantation, and US$594,520 for medical management. The mean quality-adjusted survival of lymphatic embolization yielded an additional 0.66 QALYs (P <.03) relative to heart transplantation and 1.3 (P <.0001) relative to medical management. Orthotopic heart transplantation yielded an additional 0.66 QALYs (P =.06) when comparing heart transplantation to medical management. Compared to medical management, lymphatic embolization generated an incremental cost-effectiveness ratio of US$192,105. Similarly, compared to heart transplantation, lymphatic embolization yielded an incremental cost-effectiveness ratio of US$68,030. Conclusions: Of the available plastic bronchitis treatments, with a willingness to pay of US$150,000, lymphatic embolization produces an incremental cost-effectiveness ratio within the bounds considered to be cost-effective, potentially causing financial benefits to the health system.
Keywords: azathioprine; basiliximab; cyclosporine; furosemide; mycophenolate mofetil; prednisolone; prednisone; prostacyclin; rapamycin; sildenafil; tacrolimus; thymocyte antibody; tissue plasminogen activator; article; artificial embolization; bronchitis; bronchoscopy; child; circannual rhythm; cohort analysis; computer simulation; controlled study; cost effectiveness analysis; cost utility analysis; drug cost; European Quality of Life 5 Dimensions questionnaire; government; health care utilization; health status; heart catheterization; heart transplantation; human; ICD-10; ICD-9; immunosuppressive treatment; institutional review; machine learning; modified markov model; orthotopic heart transplantation; percutaneous lymphatic embolization; plastic bronchitis; priority journal; quality adjusted life year; Rankin scale; retrospective study

Impaired pulmonary function and its association with clinical outcomes, exercise capacity and quality of life in children with congenital heart disease - Abassi, H.; Gavotto, A.; Picot, M.C.; Bertet, H.; Matecki, S.; Guillaumont, S.; Moniotte, S.; Auquier, P.; Moreau, J.; Amedro, P. (International Journal of Cardiology, 2019)
Background: Impaired pulmonary function is an independent predictor of mortality in adult congenital heart disease (CHD), but has been scarcely studied in the paediatric CHD population. Aims: To compare the pulmonary function of children with CHD to healthy controls, and evaluate its association with clinical outcomes, exercise capacity, and quality of life. Methods: Cross-sectional multicentre study among 834 children (555 CHD and 279 control subjects) who underwent a complete spirometry and a cardiopulmonary exercise test (CPET). The 5th centile (Z-score = −1.64) was used to define the lower limit of normal. The association of clinical and CPET variables with spirometry was studied using a multivariate analysis. Children and their parents filled in the Kidscreen health-related quality of life questionnaire. Results: Forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1) Z-scores values were lower in children with CHD than controls (−0.4 ± 1.5 vs. 0.4 ± 1.3, P < 0.001 and −0.5 ± 1.4 vs. 0.4 ± 1.2, P < 0.001, respectively), without any obstructive airway disorder. Restrictive pattern was more frequent in CHD patients than in controls (20% vs. 4%, P < 0.0001). FVC Z-scores were predominantly impaired in complex CHD, such as heterotaxy (−1.1 ± 0.6), single ventricle (−1.0 ± 0.2), and complex anomalies of the ventricular outflow tracts (−0.9 ± 0.1). In multivariate analysis, FVC was associated with age, body mass index, peak oxygen uptake, genetic anomalies, the number of cardiac surgery and cardiac catheter procedures. FVC and FEV1 correlated with self and proxy-related quality of life scores. Conclusion: These results suggest that pulmonary function should be monitored early in life, from childhood, in the CHD population. Trial registration number: NCT01202916, post-results.
Keywords: NCT01202916; age distribution; airway obstruction; article; body mass; child; childhood; clinical outcome; congenital heart disease; controlled study; cross-sectional study; exercise; female; forced expiratory volume; forced vital capacity; genetic disorder; heart catheterization; heart single ventricle; heart surgery; heart ventricle; heterotaxy syndrome; human; lung function; major clinical study; male; oxygen consumption; priority journal; quality of life; risk factor

The implementation of a nationwide anomaly screening programme improves prenatal detection of major cardiac defects: an 11-year national population-based cohort study - Hautala, J.; Gissler, M.; Ritvanen, A.; Tekay, A.; Pitkänen-Argillander, O.; Stefanovic, V.; Sarkola, T.; Helle, E.; Pihkala, J.; Pätilä, T.; Mattila, I.P.; Jokinen, E.; et al. (BJOG: An International Journal of Obstetrics and Gynaecology, 2019)
Objective: To evaluate whether a nationwide prenatal anomaly screening programme improves detection rates of univentricular heart (UVH) and transposition of great arteries (TGA), and whether maternal risk factors for severe fetal heart disease affect prenatal detection. Design: Population-based cohort study. Setting: Nationwide data from Finnish registries 2004–14. Population: A total of 642 456 parturients and 3449 terminated pregnancies due to severe fetal anomaly. Methods: Prenatal detection rates were calculated in three time periods (prescreening, transition and screening phase). The effect of maternal risk factors (obesity, in vitro fertilisation, pregestational diabetes and smoking) was evaluated. Main outcome measures: Change in detection rates and impact of maternal risk factors on screening programme efficacy. Results: In total, 483 cases of UVH and 184 of TGA were detected. The prenatal detection rate of UVH increased from 50.4% to 82.8% and of TGA from 12.3% to 41.0% (P < 0.0001). Maternal risk factors did not affect prenatal detection rate, but detection rate differed substantially by region. Conclusions: A nationwide screening programme improved overall UVH and TGA detection rates, but regional differences were observed. Obesity or other maternal risk factors did not affect the screening programme efficacy. The establishment of structured guidelines and recommendations is essential when implementing the screening programme. In addition, a prospective screening register is highly recommended to ensure high quality of screening. Tweetable abstract: Implementation of a nationwide prenatal anomaly screening improved detection rates of UVH and TGA.
Keywords: adult; article; cohort analysis; congenital heart malformation; controlled study; female; fetus outcome; fetus risk; great vessels transposition; heart single ventricle; high risk infant; human; in vitro fertilization; major clinical study; maternal obesity; maternal smoking; pregnancy diabetes mellitus; pregnancy termination; prenatal diagnosis; prenatal screening; priority journal; program evaluation; risk assessment; risk factor

Non-Vitamin K antagonist oral anticoagulants in adults with a Fontan circulation: Are they safe - Yang, H.; Veldtman, G.R.; Bouma, B.J.; Budts, W.; Niwa, K.; Meijboom, F.; Scognamiglio, G.; Egbe, A.C.; Schwerzmann, M.; Broberg, C.; Morissens, M.; Buber, J.; et al. (Open Heart, 2019)
Background In Fontan patients with atrial arrhythmias (AA), non-Vitamin K antagonist oral anticoagulants(NOACs) have a class III recommendation according to the Pediatric & Congenital Electrophysiology Society (PACES)/Heart Rhythm Society (HRS) guideline in 2014, due to lack of data on outcomes as opposed to evidence of harm. To address this gap in data, we investigated the safety and efficacy of NOACs in adults with a Fontan circulation in a worldwide study. Methods This is an international multicentre prospective cohort study, using data from the NOTE (non-Vitamin K antagonist oral anticoagulants for thromboembolic prevention in patients with congenital heart disease) registry. The study population comprised consecutive adults with a Fontan circulation using NOACs. Follow-up took place at 6 months and yearly thereafter. The primary endpoints were thromboembolism and major bleeding. Secondary endpoint was minor bleeding. Results From April 2014 onward, 74 patients (mean age 32±10 years (range 18-68), 54% male) with a Fontan circulation using NOACs were included. During a median follow-up of 1.2 (IQR 0.8-2.0) years, three thromboembolic events (2.9 per 100 patient-years (95% CI 0.7 to 7.6)) and three major bleedings (2.9 per 100 patient-years (95% CI 0.7 to 7.6)) occurred in five atriopulmonary Fontan and one total cavopulmonary connection Fontan patients with AA. Fifteen patients experienced minor bleeding episodes (15.8 per 100 patient-years (95% CI 9.1 to 25.2)). In patients (n=37) using Vitamin K antagonists (VKAs) prior to the initiation of NOAC, annual incidence of historical thromboembolic events and major bleeding were 2.4% (95% CI 0.4% to 7.4%) (n = 2) and 1.2% (95% CI 0.7% to 5.1%) (n = 1), respectively. Conclusions In this review of the largest Fontan cohort using NOACs with prospective follow-up, NOACs appear to be well tolerated and their efficacy and safety during short-term follow-up seem comparable to VKAs. Longer term data are required to confirm these promising short-term results.
Keywords: acetylsalicylic acid; anticoagulant agent; antithrombocytic agent; antivitamin K; dabigatran; edoxaban; nonsteroid antiinflammatory agent; rivaroxaban; adult; aged; alcohol consumption; article; atriopulmonary connection; bleeding; brain ischemia; cavopulmonary connection; cerebrovascular accident; CHA2DS2-VASc score; congenital heart disease; controlled study; deep vein thrombosis; double inlet left ventricle; drug efficacy; drug safety; epistaxis; female; follow up; Fontan procedure; gastrointestinal hemorrhage; gingiva bleeding; headache; heart atrium arrhythmia; heart failure; heart right ventricle double outlet; hematoma; human; hypertension; inferior cava vein; international normalized ratio; intracardiac thrombosis; kidney function; liver function; lung embolism; major clinical study; male; menorrhagia; multicenter study; observational study; postoperative hemorrhage; primary prevention; priority journal; prospective study; pulmonary valve atresia; risk factor; secondary prevention; skin bleeding; superior cava vein; survival analysis; thromboembolism; thrombosis prevention; transient ischemic attack; tricuspid valve atresia; vasculitis; vein thrombosis

"I'm Sticking With You, Doc" - Chiakpo, E. (Family medicine, 2019)
Keywords: antidiabetic agent; metformin; female; fertility; general practice; human; hypoplastic left heart syndrome; newborn; obstetric delivery; ovary polycystic disease; palliative therapy; perinatal death; pregnancy; psychology

Gestational age, birth weight, and outcomes six years after the norwood procedure - Miller, T.A.; Ghanayem, N.S.; Newburger, J.W.; McCrindle, B.W.; Hu, C.; DeWitt, A.G.; Cnota, J.F.; Tractenberg, F.L.; Pemberton, V.L.; Wolf, M.J.; Votava-Smith, J.K.; Fifer, C.G.; et al. (Pediatrics, 2019)
BACKGROUND: Preterm delivery and low birth weight (LBW) are generally associated with worse outcomes in hypoplastic left heart syndrome (HLHS), but an individual preterm or small neonate may do well. We sought to explore the interactions between gestational age, birth weight, and birth weight for gestational age with intermediate outcomes in HLHS. METHODS: We analyzed survival, growth, neurodevelopment, length of stay, and complications to age 6 years in subjects with HLHS from the Single Ventricle Reconstruction trial. Univariate and multivariable survival and regression analyses examined the effects and interactions of LBW (,2500 g), weight for gestational age, and gestational age category. RESULTS: Early-term delivery (n = 234) was more common than term (n = 219) delivery. Small for gestational age (SGA) was present in 41% of subjects, but only 14% had LBW. Preterm, compared with term, delivery was associated with an increased risk of death or transplant at age 6 years (all: hazard ratio = 2.58, confidence interval = 1.43–4.67; Norwood survivors: hazard ratio = 1.96, confidence interval = 1.10–3.49) independent of LBW and weight for gestational age. Preterm delivery, early-term delivery, LBW, and SGA were each associated with lower weight at 6 years. Neurodevelopmental outcomes were worst in the LBW cohort. CONCLUSIONS: Preterm delivery in HLHS was associated with worse survival, even beyond Norwood hospitalization. LBW, SGA, and early-term delivery were associated with worse growth but not survival. LBW was associated with worse neurodevelopment, despite similar length of stay and complications. These data suggest that preterm birth and LBW (although often concomitant) are not equivalent, impacting clinical outcomes through mechanisms independent of perioperative course complexity.
Keywords: article; birth weight; Blalock Taussig shunt; child; child growth; child hospitalization; cohort analysis; controlled study; death; descriptive research; female; gestational age; human; hypoplastic left heart syndrome; infant; length of stay; low birth weight; major clinical study; male; nerve cell differentiation; Norwood procedure; obstetric delivery; postoperative period; premature labor; priority journal; quality of life; right ventricle to pulmonary artery conduit; small for date infant; survival; treatment outcome

Visual-spatial processing style is associated with psychopathology in adolescents with critical congenital heart disease - Cassidy, A.R.; Bernstein, J.H.; Bellinger, D.C.; Newburger, J.W.; DeMaso, D.R. (The Clinical neuropsychologist, 2019)
OBJECTIVE: To determine whether visual-spatial processing style is associated with psychopathology in a large sample of adolescents with critical congenital heart disease (CHD). Local (part-oriented) style was hypothesized to increase risk for internalizing (but not externalizing) forms of psychopathology. METHOD: Participants included 278 adolescents with critical CHD (dextro-transposition of the great arteries = 134, tetralogy of Fallot = 58, single-ventricle cardiac anatomy requiring the Fontan procedure = 86). Visual-spatial processing style was indexed using Copy Style Ratings from the Rey-Osterrieth Complex Figure-Developmental Scoring System. The Schedule for Affective Disorders and Schizophrenia for School-Aged Children-Present & Lifetime Version was used to determine presence/absence of diagnosable DSM-IV psychiatric disorder(s). Processing style and psychopathology were assessed concurrently. RESULTS: Thirty-three percent of the sample had a part-oriented processing style. In multivariable binary logistic regression models, part-orientation was associated with more than twice the odds of having an anxiety disorder (lifetime: OR = 2.2, p = .02, 95% CI = 1.1-4.1; current: OR = 2.7, p = .03, 95% CI = 1.1-6.5) but was not associated with an increased risk for ADHD, disruptive behavior, or mood disorders (ps > .05). CONCLUSIONS: Adolescents with critical CHD who approach complex visual-spatial materials in a local, part-oriented fashion are more likely to meet criteria for an anxiety disorder than those who approach complexity more holistically. Part-orientation may make it more difficult for individuals to judge the relative importance of isolated details and engage in more adaptive perspective-taking.
Keywords: adolescent; congenital heart malformation; female; human; male; mental disease; physiology; procedures; psychology; spatial behavior; vision

The utility of potassium monitoring in gender-diverse adolescents taking spironolactone - Millington, K.; Liu, E.; Chan, Y.-M. (Journal of the Endocrine Society, 2019)
Context: Current guidelines recommend close monitoring of electrolytes in transgender patients using spironolactone given the risk of hyperkalemia from mineralocorticoid antagonism. In patients taking spironolactone for other conditions, the rate of hyperkalemia is low, and the utility of frequent monitoring has been questioned. Objective: We hypothesized that the rate of hyperkalemia in gender-diverse adolescents taking spironolactone is low and, when present, clinically insignificant. Design and Outcomes: A retrospective chart review of adolescents seen in a specialty gender clinic at a tertiary care pediatric hospital over 10 years identified patients prescribed spironolactone for gender transition. Study outcomes were the incidence of hyperkalemia, defined as serum potassium concentration .5.0 mmol/L, and the relationship between potassium levels and spironolactone dose and duration. Results: Records were reviewed for 85 subjects with a mean 6 SD age of 16.6 6 1.7 years. There were a total of 269 potassium measurements (80 prior to spironolactone initiation and 189 during spironolactone treatment). Six potassium measurements in five subjects were .5.0 mmol/L, indicating a rate of hyperkalemia of 2.2%. None of the subjects had symptoms of hyperkalemia, and all elevated measurements were normal when repeated. Only one subject discontinued spironolactone after an elevated potassium measurement. There was no relationship between hyperkalemia and spironolactone dose. Potassium measurements decreased with increasing treatment duration. Conclusions: Hyperkalemia in patients taking spironolactone for gender transition is rare and when present is transient and asymptomatic. In the absence of other medical comorbidities, routine electrolyte monitoring in this population may be unnecessary.
Keywords: potassium; spironolactone; adolescent; article; asthma; cohort analysis; comorbidity; congestive heart failure; drug withdrawal; eosinophilic esophagitis; female; gender dysphoria; gender identity; hemolysis; human; hyperkalemia; hypertension; hypoplastic left heart syndrome; low drug dose; macrophage activation syndrome; major clinical study; male; medical record review; migraine; narcolepsy; patient monitoring; potassium blood level; priority journal; retrospective study; risk factor; transgender; treatment duration

Third Annual Pediatric Interagency Registry for Mechanical Circulatory Support (Pedimacs) Report: Preimplant Characteristics and Outcomes - Morales, D.L.S.; Rossano, J.W.; VanderPluym, C.; Lorts, A.; Cantor, R.; St. Louis, J.D.; Koeh, D.; Sutcliffe, D.L.; Adachi, I.; Kirklin, J.K.; Rosenthal, D.N.; Blume, E.D. (Annals of Thoracic Surgery, 2019)
Background: The influence of ventricular assist device (VAD) use in the care of children with end-stage heart failure is growing rapidly through increasing numbers, new devices, expanding indications, and improving outcomes. Pediatric Interagency Registry for Mechanical Circulatory Support (Pedimacs), a National Institutes of Health–sponsored United States database, provides a platform to understand this emerging population. Methods: Between September 19, 2012, and December 31, 2017, 30 hospitals implanted 508 devices in 423 patients aged younger than 19 years. This past year was one of evolution for the database as its management was transitioned to The Society of Thoracic Surgery; therefore, this report does not include data from institutions not under contract by August 1, 2018. Results: Of the 423 patients, the diagnosis was cardiomyopathy in 261 (62%), myocarditis in 48 (11%), other in 28 (7%), and congenital heart disease (CHD) in 86 (20%), with 52 of these patients having single-ventricle physiology. The two most common support strategies included left VAD in 342 (81%) and biventricular assist device in 64 (15%). Positive outcome (alive on device or bridge to transplantation/recovery) was 80% at 6 months (overall mortality of 20%). The patient cohort for implantable continuous-flow (IC) pumps (n = 197; age at implant, 13.4 ± 3.8 years; 19% Interagency Registry for Mechanically Assisted Circulatory Support [Intermacs] profile 1, 21% intubated at implant, and 12% with CHD) was significantly different from the paracorporeal continuous-flow (PC) pump cohort (n = 79; age, 3.9 ± 5.2 years; 49% Intermacs profile 1, 86% intubated at implant, and 38% with CHD) and the paracorporeal pulsatile (PP) pump cohort (n = 121; age, 3.3 ± 3.9 years; 41% Intermacs profile 1, 77% intubated at implant, and 21% with CHD). Consistent with their cohort composition, device type positive outcomes at 6 months were PC, 63%; PP, 77%; and IC, 92%. Parametric hazard modeling showed an early hazard for death was associated with Intermacs profile 1, biventricular assist device, percutaneous devices, PC devices, small-volume institutions, low age, and low weight, whereas a constant hazard was associated with intubation and liver dysfunction at time of implant. Conclusions: IC VADs are the most common VAD type placed in children. The positive outcomes for the IC VADs exceed 90% at 6 months, which may represent our field's maturation in both patient selection and timing of implantation. The PP/PC devices are currently limited to supporting our most challenging patients, those weighing less than 20 kg and those with CHD. The introduction of new devices and our communities’ commitment to shared learning and improvement will lead to more pediatric lives saved by VAD support and will also focus on improving the quality of life of children supported with VADs.
Keywords: biventricular assist device; left ventricular assist device; adolescent; adult; article; assisted circulation; bleeding; brain hemorrhage; brain ischemia; cardiogenic shock; cardiomyopathy; cause of death; cerebrovascular accident; child; cohort analysis; congenital heart disease; device malfunction; extracorporeal oxygenation; hospitalization; human; implantation; infection; liver dysfunction; major clinical study; mechanical circulatory support; medical device complication; mortality; multiple organ failure; myocarditis; neurologic disease; postoperative period; preschool child; priority journal; register; young adult

Neurodevelopmental outcome in hypoplastic left heart syndrome after hybrid procedure - Reich, B.; Heye, K.N.; Wetterling, K.; Logeswaran, T.; Hahn, A.; Akintürk, H.; Jux, C.; Schranz, D. (Translational Pediatrics, 2019)
Background: Little is known about the mid-term outcome and brain development in patients following the hybrid approach for hypoplastic left heart syndrome (HLHS). This study investigates neurodevelopmental outcome, quality of life (QoL) and brain MRI findings in HLHS preschoolers treated with the hybrid approach. Methods: Twenty HLHS patients (60% males) have been examined after neonatal hybrid Stage I and comprehensive stage II operation at the Pediatric Heart Center Giessen, Germany, between 2012 and 2016. Patients were evaluated with the Bayley Scales of Infant and Toddler Development III (Bayley-III), neurological examination, the Preschool Children Quality of Life Questionnaire (TAPQOL) at age 26.5±3.6 months, and again at 39.7±3.9 months with the Pediatric Cardiac Quality of Life Inventory (PCQLI). Furthermore, brain volumetric measurements and conventional brain MRI findings (27.3±4.5 months) were analyzed and compared with six healthy controls (29.2±11.1 months, P=0.53). Children with verified genetic comorbidities were excluded. Results: Mean cognitive, language, and motor composite scores on the Bayley-III were not different from healthy norms (100±15), and were 101±9.3 (P=0.48), 100±13 (P=0.93), and 98±11.7 (P=0.45), respectively. Status post stroke was the most common brain MRI abnormality, and was found in 3/19 (16%) patients, most common affecting the middle cerebral artery territory. In comparison to controls, total white matter volumes were reduced (P=0.014), and cerebrospinal fluid (CSF) volumes were increased (P=0.042) in patients. Overall health-related QoL in 2 to 3 years aged children HLHS was good, but inferior scores in the motor subscale were noted compared to healthy norms (P=0.007). However, at 3 to 4 years, parents reported comparable QoL for their children in the PCQLI to children with biventricular heart lesion. Conclusions: HLHS patients followed by hybrid approach without major complications show a favorable neurodevelopment at 2–3 years of age. Despite extensive health-related burden, the vast majority of Fontan preschoolers with HLHS showed a good health-related QoL. Nevertheless, comprehensive care and establishing routine follow-up examinations are important to recognize long-term challenges and further improve neurodevelopmental outcome of this high-risk patient population.
Keywords: Magnetom Verio B17; nuclear magnetic resonance scanner; article; Bayley Scales of Infant Development; cerebrospinal fluid; cerebrovascular accident; child; clinical article; clinical assessment; cognition; controlled study; female; human; hypoplastic left heart syndrome; language; male; middle cerebral artery; motor activity; nerve cell differentiation; nuclear magnetic resonance imaging; pediatric cardiac quality of life inventory; preschool children quality of life questionnaire; quality of life; questionnaire; surgical approach; volumetry; Magnetom Verio B17

149 Fontan Conversions - Backer, C.L.; Mavroudis, C. (Methodist DeBakey cardiovascular journal, 2019)
Patients with a functionally univentricular heart who have had an atriopulmonary Fontan are at risk for atrial dilatation, atrial arrhythmias, and progressive circulatory failure. Between 1994 and 2018, we performed 149 Fontan conversions with arrhythmia surgery and epicardial pacemaker placement at Ann & Robert H. Lurie Children's Hospital of Chicago. This operation converts the atriopulmonary Fontan to an extracardiac Fontan that improves hemodynamics and controls the atrial arrhythmias. Operative mortality during that time was 2%, and freedom from death or heart transplant at 10 years is 84%. For properly selected patients, Fontan conversion improves both survival and quality of life. Patients with an atriopulmonary Fontan constitute an eroding population, as they face many comorbidities and have a decreased life expectancy without treatment; therefore, all patients with an atriopulmonary Fontan should be evaluated for this procedure.
Keywords: adolescent; adult; cardiomegaly; child; clinical decision making; complication; congenital heart malformation; female; Fontan procedure; heart arrhythmia; human; male; middle aged; mortality; pathophysiology; patient selection; preschool child; reoperation; risk assessment; risk factor; time factor; young adult

Outcomes and associated ethical considerations of long-run pediatric ECMO at a single center institution - Ares, G.J.; Buonpane, C.; Helenowski, I.; Reynolds, M.; Hunter, C.J. (Pediatric Surgery International, 2019)
Purpose: Survival of neonatal and pediatric patients undergoing extracorporeal membrane oxygenation (ECMO) ≥ 21 days has not been well described. We hypothesized that patients would have poor survival and increased long-term complications. Methods: Retrospective, single center, review and case analysis. Tertiary-care university children’s hospital including neonatal, pediatric and cardiac intensive care units. After institutional review board approval, the charts of all patients < 18 years of age undergoing ECMO for ≥ 21 continuous days were performed, and they were compared to comparative patients undergoing shorter runs. Overall survival, incidence of complications, and post-discharge recovery were recorded. Results: Overall survival was 36% in patients undergoing ≥ 21 days of ECMO (N = 14). 5/8 patients with cardiopulmonary failure from acquired etiologies survived versus 0/6 patients with congenital anomalies. 1/5 survivors achieved complete recovery with no neurologic deficits. The remaining survivors suffer from multiple medical and neurodevelopmental morbidities. Conclusion: ECMO support for ≥ 21 days is associated with poor survival, particularly in neonates with congenital anomalies. Long-term outcomes for survivors ought to be carefully weighed and discussed with parents given the high incidence of neurologic morbidities in this population.
Keywords: above knee amputation; adult; article; bacterial pneumonia; brain hemorrhage; brain ischemia; cardiopulmonary arrest; child; clinical article; clinical outcome; congenital malformation; convalescence; coronary care unit; developmental delay; diaphragm hernia; extracorporeal oxygenation; female; heart failure; human; hypoplastic left heart syndrome; learning disorder; leg ischemia; lung dysplasia; lung hemorrhage; male; medical ethics; medical record review; mental disease; middle aged; morbidity; myositis; necrotizing pneumonia; overall survival; pediatric intensive care unit; persistent pulmonary hypertension; pertussis; preschool child; priority journal; retrospective study; school child; superinfection; tension pneumothorax; thoracostomy; thrombosis; virus pneumonia

Amiodarone toxicity in two post-operative congenital heart disease patients - Covi, S.; Clark, J.; Delius, R.; Chauhan, M. (Progress in Pediatric Cardiology, 2019)
Amiodarone is a class III antiarrhythmic medication known for its efficacy in treating tachyarrhythmias. The pulmonary complications including acute lung toxicity are well documented in the adult population, however much less so in pediatrics. We describe two pediatric congenital heart disease patients with suspected amiodarone induced pulmonary toxicity in the post-operative period. Case 1 presented with acute respiratory distress syndrome accompanied by periods of pulmonary hemorrhage post-operatively; after multiple courses of methylprednisolone and discontinuation of amiodarone, she showed significant clinical improvement with normalization of her CXR. Case 2 presented as hypoxemic with acute respiratory distress syndrome, and had notable clinical improvement after cessation of amiodarone with pulse dose methylprednisolone and inhaled budesonide.
Keywords: amiodarone; budesonide; hydrocortisone; methylprednisolone; prednisone; propranolol; adolescent; adult respiratory distress syndrome; article; bronchoscopy; case report; clinical article; drug dose reduction; drug withdrawal; Ebstein anomaly; echocardiography; extubation; female; follow up; Glenn shunt; heart ventricle tachycardia; human; hypoplastic left heart syndrome; hypoxemia; loading drug dose; lung hemorrhage; lung lavage; lung toxicity; priority journal; thorax radiography; tricuspid annuloplasty; tricuspid valve replacement

“It's not one size fits all”; the use of videoconferencing for delivering therapy in a Specialist Paediatric Chronic Fatigue Service - Haig-Ferguson, A.; Loades, M.; Whittle, C.; Read, R.; Higson-Sweeney, N.; Beasant, L.; Starbuck, J.; Crawley, E. (Internet Interventions, 2019)
Background: There are few specialist paediatric Chronic Fatigue Syndrome (CFS/ME) services in the UK. Therefore, the distance some families have to travel to reach these services can be a barrier to accessing evidence-based treatment. Videoconferencing technology such as Skype provides a means of delivering sessions remotely. This study aimed to explore the views of children and young people, their parents, and healthcare professionals of treatment delivered by videoconferencing in a specialist paediatric CFS/ME team. Method: To explore the experiences of the participants, a qualitative design was selected. Twelve young people (age 9–18), and 6 parents were interviewed about their experience of treatment sessions delivered via videoconferencing within a specialist CFS/ME service. A focus group explored the views of healthcare professionals (N = 9) from the service. Thematic analysis was used. Results: Three themes were identified from the data: “Challenges and concerns” “Benefits” and “Treatment provision”. Challenges and concerns that participants identified were; difficulties experienced with technology; a sense of a part of communication being lost with virtual connections; privacy issues with communicating online and feeling anxious on a screen. Participants felt that benefits of videoconferencing were; improving access to the chronic fatigue service; convenience and flexibility of treatment provision; a sense of being more open online and being in the comfort of their own home. In terms of treatment provision participants talked about videoconferencing as a part of a hierarchy of communication; the function of videoconferencing within the context of the chronic fatigue service; additional preparation needed to utilise videoconferencing and an assumption that videoconferencing is “part of young people's lives”. Conclusions: Although the experience of sessions provided by videoconferencing was different to sessions attended in person, participants tended to be positive about videoconferencing as an alternative means of accessing treatment, despite some barriers. Videoconferencing could be an additional option within an individualised care plan, but should not be an alternative to face to face support.
Keywords: adolescent; adult; article; atriopulmonary connection; behavior change; child; chronic fatigue syndrome; clinical article; clinical assessment; clinical evaluation; emotionality; evaluation and follow up; evidence based emergency medicine; female; geographic distribution; health care delivery; health care personnel; health care planning; health service; human; interview; male; mental health; occupational therapy; pediatrics; physiotherapy; priority journal; privacy; psychology; qualitative analysis; research; school child; social hierarchy; technology; teleconsultation; thematic analysis; training; videoconferencing; young adult

Comment on the original paper entitled “Can a home-based cardiac physical activity program improve and sustain quality of life and exercise capacity in children with Fontan circulation?” - Callegari, A.; Christmann, M. (Progress in Pediatric Cardiology, 2019)
Commentary on the original paper entitled “Can a home-based cardiac physical activity program improve and sustain quality of life and exercise capacity in children with Fontan circulation?”
Keywords: article; child; exercise; heart; human; physical activity; quality of life; respiratory function

Neurodevelopmental assessment of infants with congenital heart disease in the early postoperative period - Butler, S.C.; Sadhwani, A.; Stopp, C.; Singer, J.; Wypij, D.; Dunbar-Masterson, C.; Ware, J.; Newburger, J.W. (Congenital Heart Disease, 2019)
Objective: Mortality rates for children with congenital heart disease (CHD) have significantly declined, resulting in a growing population with associated neurodevelopmental disabilities. American Heart Association guidelines recommend systematic developmental screening for children with CHD. The present study describes results of inpatient newborn neurodevelopmental assessment of infants after open heart surgery. Outcome measures: We evaluated the neurodevelopment of a convenience sample of high-risk infants following cardiac surgery but before hospital discharge using an adaptation of the Newborn Behavioral Observation. Factor analysis examined relationships among assessment items and consolidated them into domains of development. Results: We assessed 237 infants at a median of 11 days (interquartile range [IQR]: 7-19 days) after cardiac surgery and median corrected age of 21 days (IQR: 13-33 days). Autonomic regulation was minimally stressed or well organized in 14% of infants. Upper and lower muscle tone was appropriate in 33% and 35%, respectively. Appropriate response to social stimulation ranged between 7% and 12% depending on task, and state regulation was well organized in 14%. The vast majority (87%) required enhanced examiner facilitation for participation. Factor analyses of assessment items aligned into four domains of development (autonomic, motor, oral motor, and attention organization). Conclusion: At discharge, postoperative infants with CHD had impairments in autonomic, motor, attention, and state regulation following cardiac surgery. Findings highlight the challenges faced by children with CHD relative to healthy peers, suggesting that neurodevelopmental follow-up and intervention should begin early in infancy.
Keywords: aortic coarctation; article; attention; clinical assessment tool; cohort analysis; congenital heart disease; controlled study; cross-sectional study; facilitation; factor analysis; Fallot tetralogy; female; gestational age; great vessels transposition; heart catheterization; heart single ventricle; heart ventricle septum defect; high risk infant; hospital discharge; hospital patient; human; hypoplastic left heart syndrome; infant; major clinical study; male; motor performance; muscle tone; newborn; Newborn Behavioral Observation; open heart surgery; postoperative period; priority journal; regulatory mechanism; seizure; stimulus response

An innovative ventricular assist device strategy as a bridge-to-recovery in an infant with glenn physiology - Boston, U.; Sun, J.X.; Kumar, T.K.S.; Knott-Craig, C. (ASAIO Journal, 2019)
Mechanical circulatory support for infants with single ventricle physiology remains challenging. Utilization of a ventricular assist device (VAD) has potential advantages over extracorporeal circulatory membrane oxygenation. As such, VAD utilization in single ventricle patients with refractory heart failure continues to be explored. Herein, we describe a novel VAD strategy to support an infant with Glenn physiology who presented in cardiogenic shock related to myocardial depression of unknown etiology. This VAD configuration supported the systemic circulation independent of the Glenn circulation. Seven days of VAD support resulted in recovery of myocardial and end-organ function leading to VAD removal. The patient remains alive and free from transplantation 16 months post VAD explantation.
Keywords: ventricular assist device; milrinone; article; cardiogenic shock; depression; device removal; explant; flow rate; heart ejection fraction; heart function; heart ventricle contractility; heart ventricle function; human; implantation; infant; myocardial disease; physiology; priority journal; systemic circulation; transplantation; weaning

The Case for Cardiac Xenotransplantation in Neonates: Is Now the Time to Reconsider Xenotransplantation for Hypoplastic Left Heart Syndrome? - Cleveland, D.; Adam Banks, C.; Hara, H.; Carlo, W.F.; Mauchley, D.C.; Cooper, D.K.C. (Pediatric Cardiology, 2019)
Neonatal cardiac transplantation for hypoplastic left heart syndrome (HLHS) is associated with excellent long-term survival compared to older recipients. However, heart transplantation for neonates is greatly limited by the critical shortage of donor hearts, and by the associated mortality of the long pre-transplant waiting period. This led to the development of staged surgical palliation as the first-line surgical therapy for HLHS. Recent advances in genetic engineering and xenotransplantation have provided the potential to replicate the excellent results of neonatal cardiac allotransplantation while eliminating wait-list-associated mortality through genetically modified pig-to-human neonatal cardiac xenotransplantation. The elimination of the major pig antigens in addition to the immature B-cell response in neonates allows for the potential to induce B-cell tolerance. Additionally, the relatively mature neonatal T-cell response could be reduced by thymectomy at the time of operation combined with donor-specific pig thymus transplantation to “reprogram” the host’s T-cells to recognize the xenograft as host tissue. In light of the recent significantly increased graft survival of genetically-engineered pig-to-baboon cardiac xenotransplantation, we propose that now is the time to consider devoting research to advance the potential clinical application of cardiac xenotransplantation as a treatment option for patients with HLHS. Employing cardiac xenotransplantation could revolutionize therapy for complex congenital heart defects and open a new chapter in the field of pediatric cardiac transplantation.
Keywords: article; health care cost; heart single ventricle; heart transplantation; high risk population; human; hypoplastic left heart syndrome; intermethod comparison; length of stay; long term care; mortality rate; newborn; nonhuman; palliative therapy; quality of life; reoperation; survival rate; thymus; transplantation tolerance; treatment outcome; xenotransplantation

Hybrid transcatheter tricuspid valve-in-valve placement of an Edwards Sapien XT valve in palliated hypoplastic left heart syndrome - Ho, A.B.; Kaarne, M.; Mullen, M.; Hayes, N. (Catheterization and Cardiovascular Interventions, 2019)
Tricuspid regurgitation in the context of hypoplastic left heart syndrome (HLHS) carries a significant burden of both mortality and morbidity. We report successful hybrid trans-atrial implantation of an Edwards Sapien XT valve into a dysfunctional bioprosthetic valve in the tricuspid position of a 9-year-old patient with HLHS. There was an immediate fall in the Fontan pressures combined with significant clinical improvement and the valve continues to function well nearly 3 years post implant. To the best of our knowledge, this is the first described implantation of a transcatheter valve in this specific position and anatomy.
Keywords: Amplatzer sizing balloon; angiographic catheter; CarboMedics prosthetic heart valve; CarboMedics prosthetic heart valve; Carpentier Edwards bioprosthesis; Carpentier-Edwards Perimount Magna Ease; catheter sheath; guide wire; pacemaker electrode; percutaneous aortic valve; sizing balloon catheter; Terumo; HLA antibody; warfarin; angiography; article; case report; cavopulmonary connection; child; clinical article; complete heart block; exercise tolerance; heart transplantation; human; hypoplastic left heart syndrome; jugular vein thrombosis; loss of appetite; male; New York Heart Association class; Norwood procedure; operation duration; preschool child; prosthetic valve dysfunction; prosthetic valve thrombosis; school attendance; school child; transesophageal echocardiography; transthoracic echocardiography; tricuspid valve regurgitation; tricuspid valve repair; tricuspid valve replacement; Amplatzer sizing balloon; Carbomedics valve; Carpentier-Edwards Perimount Magna Ease; Edwards Sapien XT; Judkins; Terumo

Need for Routine Screening of Health-Related Quality of Life in Families of Young Children with Complex Congenital Heart Disease - Denniss, D.L.; Sholler, G.F.; Costa, D.S.J.; Winlaw, D.S.; Kasparian, N.A. (Journal of Pediatrics, 2019)
Objectives: To assess health-related quality of life (HRQOL) in families of young children with complex congenital heart disease (CHD), and identify the demographic, clinical, and psychosocial factors that place these children and their mothers at greater risk of vulnerability. Study design: This cross-sectional study took place from June 2015 to October 2016 at The Sydney Children's Hospitals Network Cardiac Service, Australia. Mothers of a child aged 1-5 years with either single ventricle CHD or CHD requiring neonatal biventricular repair were invited to participate. Eighty-seven mothers completed a suite of validated measures, including the Pediatric Quality of Life Inventory, which assessed the outcomes of child and maternal HRQOL. Results: Sixty percent of children with single ventricle CHD and 25% of children with biventricular repair had total Pediatric Quality of Life Inventory scores within the at-risk range. Lower child HRQOL was strongly associated with single ventricle CHD (β = −0.38; P <.001), physical comorbidity (β = −0.32; P =.001), feeding difficulties (β = −0.26; P =.008), and greater maternal psychological stress (β = −0.18; P =.045), accounting for 52% of the variance in child HRQOL. Lower maternal HRQOL was strongly associated with poorer family functioning (β = 0.61; P <.001), greater maternal psychological stress (β = −0.23; P =.004), child physical comorbidity (β = −0.17; P =.01), and a ‘difficult’ child temperament (β = −0.14; P =.01), accounting for 73% of the variance in maternal HRQOL. Conclusions: Lower HRQOL is common in young children with complex CHD, particularly single ventricle CHD. Several predictors of HRQOL are potentially modifiable, offering possible pathways for prevention and early intervention. Routine screening is a necessary first step toward developing models of care to improve HRQOL in this population.
Keywords: adult; article; Australia; child; comorbidity; congenital heart disease; cross-sectional study; family functioning; feeding difficulty; female; heart single ventricle; human; male; mental stress; Pediatric Quality of Life Inventory; priority journal; quality of life; social psychology; temperament

Outcomes of the conversion of the fontan-kreutzer operation to a total cavopulmonary connection for the failing univentricular circulation - Fernandes, G.C.; da Silva, G.V.R.; Caneo, L.F.; Tanamati, C.; Turquetto, A.L.R.; Jatene, M.B. (Arquivos Brasileiros de Cardiologia, 2019)
Background: The Fontan-Kreutzer procedure (FK) was widely performed in the past, but in the long-term generated many complications resulting in univentricular circulation failure. The conversion to total cavopulmonary connection (TCPC) is one of the options for treatment. Objective: To evaluate the results of conversion from FK to TCPC. Methods: A retrospective review of medical records for patients who underwent the conversion of FK to TCPC in the period of 1985 to 2016. Significance p < 0,05. Results: Fontan-type operations were performed in 420 patients during this period: TCPC was performed in 320, lateral tunnel technique in 82, and FK in 18. Ten cases from the FK group were elected to conversion to TCPC. All patients submitted to Fontan Conversion were included in this study. In nine patients the indication was due to uncontrolled arrhythmia and in one, due to protein-losing enteropathy. Death was observed in the first two cases. The average intensive care unit (ICU) length of stay (LOS) was 13 days, and the average hospital LOS was 37 days. A functional class by New York Heart Association (NYHA) improvement was observed in 80% of the patients in NYHA I or II. Fifty-seven percent of conversions due to arrhythmias had improvement of arrhythmias; four cases are cured. Conclusions: The conversion is a complex procedure and requires an experienced tertiary hospital to be performed. The conversion has improved the NYHA functional class despite an unsatisfactory resolution of the arrhythmia.
Keywords: adult; article; blood clotting disorder; bradycardia; cardiovascular surgery; cavopulmonary connection; child; cryoablation; female; Fontan procedure; heart arrhythmia; heart left ventricle volume; heart transplantation; heart ventricle function; hospitalization; human; intensive care unit; ischemia; lateral tunnel technique; length of stay; major clinical study; male; middle aged; mortality; operation duration; protein losing gastroenteropathy; quality of life; retrospective study; survival rate; univentricular circulation failure

Quality of life in young people with congenital heart disease is better than expected - Reiner, B.; Oberhoffer, R.; Ewert, P.; Müller, J. (Archives of Disease in Childhood, 2019)
Objectives Improved treatments for patients with congenital heart disease (CHD) have led to a growing interest in long-term functional outcomes such as health-related quality of life (HRQoL). Studies on HRQoL in children with CHD have contradicting results. Therefore, we compared HRQoL of children with CHD with that of current healthy peers and stratify CHD cases by severity and diagnostic subgroups. Methods We included 514 patients (191 girls) aged 7-17 (12.9±3.1) years who were recruited at our institution between July 2014 and May 2017. The self-reported and age-adapted KINDL questionnaire was used to assess HRQoL. Patient data were compared with that of a recent control group of 734 healthy children (346 girls, 13.4±2.1 years). Results Patients with CHD scored at least as high as healthy peers in HRQoL (CHD: 78.6±9.8; healthy: 75.6±10.1; P<0.001). After correction for sex and age, patients with CHD presented a 2.3-point higher HRQoL (P<0.001). The sex-specific and age-specific analyses showed that there were no differences between boys with and without CHD in childhood (P=0.255), but in adolescence, boys with CHD had on average 3.9-point higher scores (P=0.001), whereas girls with CHD had statistically higher HRQoL perception than healthy girls in childhood (4.2 points; P=0.003) and adolescence (4.2 points; P=0.005). There were no differences between the severity classes or diagnostic subgroups in the total HRQoL score or in the six subdomains. Conclusion The high HRQoL in young patients with CHD suggests that they can cope well with their disease burden. This holds true for all severity classes and diagnostic subgroups.
Keywords: adolescence; adolescent; article; atrioventricular septal defect; child; childhood; clinical outcome; congenital heart disease; developmental stage; disease severity; Fallot tetralogy; female; groups by age; heart single ventricle; heart ventricle septum defect; human; long term care; major clinical study; male; patient coding; priority journal; quality of life; quality of life assessment; school child; self esteem

Health-related quality of life in pre-school age children with single-ventricle CHD - Heye, K.N.; Knirsch, W.; Scheer, I.; Beck, I.; Wetterling, K.; Hahn, A.; Hofmann, K.; Latal, B.; Reich, B.; Landolt, M.A. (Cardiology in the Young, 2019)
Background: Little is known about health-related quality of life in young children undergoing staged palliation for single-ventricle CHD. The aim of this study was to assess the impact of CHD on daily life in pre-schoolers with single-ventricle CHD and to identify determinants of health-related quality of life. Method: Prospective two-centre cohort study assessing health-related quality of life using the Preschool Paediatric Cardiac Quality of Life Inventory in 46 children at a mean age of 38 months and 3 weeks. Children with genetic anomalies were excluded. Scores were compared with reference data of children with biventricular CHD. Multiple linear regression analysis was used to identify determinants of health-related quality of life. Results: Health-related quality of life in pre-schoolers with single-ventricle CHD was comparable to children with biventricular CHD. Preterm birth and perioperative variables were significant predictors of low health-related quality of life. Notably, pre-Fontan brain MRI findings and neurodevelopmental status were not associated with health-related quality of life. Overall, perioperative variables explained 24% of the variability of the total health-related quality of life score. Interpretation: Despite substantial health-related burden, pre-schoolers with single-ventricle CHD showed good health-related quality of life. Less-modifiable treatment-related risk factors and preterm birth had the highest impact on health-related quality of life. Long-term follow-up assessment of self-reported health-related quality of life is needed to identify patients with poorer health-related quality of life and to initiate supportive care.
Keywords: article; brain; child; clinical article; cohort analysis; controlled study; female; follow up; heart single ventricle; human; male; multiple linear regression analysis; nuclear magnetic resonance imaging; prematurity; preschool child; quality of life; risk factor

Atrioventricular reentrant tachycardia in a child with tricuspid atresia: A case report of catheter ablation - Wang, Y.; Liu, Q.; Deng, X.; Xiao, Y.; Chen, Z. (Medicine (United States), 2019)
Rationale:Atrioventricular reentrant tachycardia (AVRT) is the most common supraventricular tachycardia occurring in children. However, in complex congenital heart disease patients with a different heart anatomy and conduction system morphology, accessory pathway modification may be particularly challenging because of distortion of typical anatomic landmarks.Patient concerns:A 10-year-old boy with tricuspid atresia and history of bidirectional Glenn operation had recurrent chest distress and palpitation for 3 months. He had multiple hospitalizations for narrow-QRS tachycardia with poor hemodynamic tolerance, despite the use of adenosine and amiodarone.Diagnoses:AVRT. Tricuspid atresia with secundum atrial septal defect, large ventricular septal defect, and right ventricular outflow tract stenosis.Interventions:Cardiac catheterization, electrophysiological examination, and ablation.Outcomes:The child has not had a recurrent AVRT during 6 months of follow-up and is waiting for Fontan operation.Lessons:Since there is an increased risk of accessory pathways in patients with tricuspid atresia, all these patients should be checked before the Fontan operation to exclude congenital accessory pathways.
Keywords: ablation catheter; electrode catheter; adenosine; amiodarone; angiocardiography; article; atrioventricular nodal reentry tachycardia; case report; catheter ablation; child; clinical article; cyanosis; digital clubbing; electrocardiogram; electrophysiological procedures; follow up; Fontan procedure; Glenn shunt; heart atrium septum defect; heart catheterization; heart electrophysiology; heart outflow tract obstruction; heart palpitation; heart ventricle septum defect; His bundle electrogram; hospitalization; human; male; New York Heart Association class; oxygen saturation; paroxysmal supraventricular tachycardia; pediatric patient; physical examination; priority journal; QRS complex; school child; thorax pain; tricuspid valve atresia

Functional capacity in children and adolescents with congenital heart disease - Schaan, C.W.; Feltez, G.; D’Agord Schaan, B.; Pellanda, L.C. (Revista Paulista de Pediatria, 2019)
Objective: To evaluate the physical activity level and functional capacity of children and adolescents with congenital heart disease and to describe correlations between functionality, surgical and echocardiographic findings, metabolic and inflammatory profile and differences between acyanotic and cyanotic heart defects. Methods: A cross-sectional study including children and adolescents with congenital heart disease between six and 18 years old that were evaluated with the 6-minute walk test (6MWT) to assess functional capacity. The short version form of the International Physical Activity Questionnaire (IPAQ) was performed to evaluate physical activity levels. Also, echocardiography and blood collection, to evaluate the metabolic (blood glucose, lipids, insulin) and inflammatory markers (C-reactive protein), were assessed. Results: Twenty-five individuals were evaluated. Of them, 14 had acyanotic heart defects and 11 cyanotic heart defects. Mean age was 12.0±3.7 years, and 20 (80%) were male. IPAQ showed that six (24%) individuals were very active, eight (32%) were active, nine (36%) had irregular physical activity, and two (8%) were sedentary. The mean distance walked in the 6MWT, considering all studied individuals, was 464.7±100.4 m, which was 181.4±42.0 m less than the predicted (p=0.005). There was a positive correlation between Z score 6MWT and the number of surgical procedures (r=-0.455; p=0.022). Conclusions: Children and adolescents with congenital heart disease have low functional capacity, but they are not completely sedentary.
Keywords: biological marker; C reactive protein; glucose; insulin; lipid; adolescent; aortic coarctation; article; atrioventricular septal defect; bicuspid aortic valve; blood sampling; child; clinical article; congenital heart disease; cross-sectional study; cyanotic heart disease; echocardiography; Fallot tetralogy; female; functional status; glucose blood level; great vessels transposition; heart right ventricle double outlet; heart single ventricle; human; inflammation; international physical activity questionnaire; male; metabolism; physical activity; pulmonary valve stenosis; sedentary lifestyle; six minute walk test; walking distance

Plastic bronchitis: A case report - Grizales, C.L.; González, L.M.; Castrillon, M.A.; Sua, L.F.; Lores, J.; Aguirre, M.; Fernández-Trujillo, L. (Respiratory Medicine Case Reports, 2019)
Plastic bronchitis is a rare and underdiagnosed disease characterized by the formation and expectoration of bronchial casts of amorphous material, which can be potentially fatal. It is more frequent in pediatric population. Symptoms can range from chronic cough and dyspnea to respiratory failure depending on the area of the compromised airway. Casts are classified as type I when constituted by inflammatory cells and accompany diseases such as asthma and pneumonias; and type II when acellular and are associated with congenital heart diseases following procedures such as Fontan. We report the case of a male schoolchild with a history of complex congenital heart disease, treated with palliative surgery, evaluated in the emergency department for cough and respiratory distress. The mother referred expulsion of gelatinous material after coughing. During clinical evaluation, expulsion of bronchial casts was evidenced, suggesting a plastic bronchitis. He underwent a diagnostic and therapeutic bronchoscopy and received initial treatment with respiratory therapy, nebulized hypertonic saline solution, mucolytics, dornase alpha and nebulized heparin. The hospitalization revealed a stenosis of the right pulmonary artery, which was corrected with stent. The patient progressed satisfactorily with improvement of cough and expectoration. He was discharged with combined treatment, nebulized medications and those concerning his underlying disease.
Keywords: arterial stent; dornase alfa; heparin; sodium chloride; article; bronchitis; bronchoscopy; case report; child; clinical article; clinical evaluation; computer assisted tomography; congenital heart disease; coughing; dyspnea; edema; emergency ward; erythema; Fontan procedure; heart catheterization; hospital discharge; hospitalization; human; lung mucosa; male; medical history; oxygen therapy; palliative therapy; plastic bronchitis; priority journal; pulmonary artery stenosis; respiratory care; respiratory distress; staining; thorax radiography

Persistent hyperinsulinaemic hypoglycaemia in children with Rubinstein-Taybi syndrome - Welters, A.; El-Khairi, R.; Dastamani, A.; Bachmann, N.; Bergmann, C.; Gilbert, C.; Clement, E.; Hurst, J.A.; Quercia, N.; Wasserman, J.D.; Meissner, T.; Shah, P.; et al. (European Journal of Endocrinology, 2019)
Objective: Genetic aetiology remains unknown in up to 50% of patients with persistent hyperinsulinaemic hypoglycaemia (HH). Several syndromes are associated with HH. We report Rubinstein-Taybi syndrome (RSTS) as one of the possible causes of persistent HH. Early diagnosis and treatment of HH is crucial to prevent hypoglycaemic brain injury. Design: Four RSTS patients with HH were retrospectively analysed. Methods: Genetic investigations included next-generation sequencing-based gene panels and exome sequencing. Clinical characteristics, metabolic profile during hypoglycaemia and treatment were reviewed. Results: Disease-related EP300 or CREBBP variants were found in all patients, no pathogenic variants were found in a panel of genes associated with non-syndromic HH. Two patients had classic manifestations of RSTS, three had choanal atresia or stenosis. Diagnosis of HH varied from 1 day to 18 months of age. One patient was unresponsive to treatment with diazoxide, octreotide and nifedipine, but responded to sirolimus. All required gastrostomy feeding. Conclusions: Given the rarity of RSTS (1:125 000) and HH (1:50 000), our ob servations indicate an association between these two conditions. We therefore recommend that clinicians should be vigilant in screening for HH in symptomatic infants with RSTS. In children with an apparent syndromic form of HH, RSTS should be considered in the differential diagnosis.
Keywords: stomach tube; 6 fluorodopa f 18; acarbose; barium; C peptide; chlorothiazide; crebbp protein; diazoxide; E1A associated p300 protein; fatty acid; glucose; infusion fluid; insulin; ketone; nifedipine; octreotide; protein; rapamycin; unclassified drug; article; bradycardia; case report; cataract; choana atresia; cleft palate; clinical article; clinical feature; cyanosis; developmental delay; disease course; disease severity; drug withdrawal; dysplasia; electromyography; face dysmorphia; fatty acid blood level; feeding difficulty; female; fluoroscopy; Fontan procedure; gastroesophageal reflux; gastrostomy; genetic analysis; genetic association; genetic screening; genetic variation; gestational age; glucose blood level; glycemic control; heart atrium septum defect; heterozygote; high calorie diet; human; hypertrichosis; hypervolemia; insulin blood level; insulin release; intermittent strabismus; laryngomalacia; long philtrum; low drug dose; male; multicystic dysplastic kidney; nerve conduction; nervousness; newborn; high throughput sequencing; nuclear magnetic resonance imaging; oral glucose tolerance test; patent ductus arteriosus; pericardial effusion; persistent hyperinsulinemic hypoglycemia of infancy; positron emission tomography-computed tomography; priority journal; protein intolerance; ptosis (eyelid); retrospective study; Rubinstein syndrome; sepsis; somnolence; speech delay; stomach fundoplication; tachycardia; teratoma; tonic clonic seizure; treatment response; tricuspid valve atresia; vomiting; whole exome sequencing

Frequency of associated congenital heart defects in down syndrome - Hyder, S.N.; Humayun, L.; Hasan, A. (Pakistan Journal of Medical and Health Sciences, 2019)
Background: Children with Downs seem commonly with defects in their heart. Aim: To find out the occurrence of congenital heart disease in children with Down. Methods: This retrospective study planned at the cardiology unit in the children's hospital, Lahore, in 2017. One hundred and seven babies with Down enrolled in this study until 14 years of age. Results: Heart diseases seem in 63 patients from 107 that revealed 59% with male to female ratio of 1.7:1. Among the isolated single lesions ventricular septal defect found in 60.3% patent ductus arteriosus in 13.7%, complete atrioventricular defects in 8.6%, followed by ASD in 6.8%, Pulmonary atresia with VSD in 6.8%,Tetralogy of Fallot and TGA in 1.7% of patients. Among the mixed lesion (4.7%) VSD+ASD found in two patients while COA+ PDA, Univentricular heart with TGA and PA+VSD +DORV found in each patients. Conclusion: Heart lesion in down babies seen to be 59%. In non-cyanotic lesion, ventricular septal defect was common, while in category of cyanotic heart lesion the pulmonary atresia and VSD was found and in mix heart lesion VSD with ASD was found.
Keywords: aortic coarctation; article; child; childhood disease; congenital heart malformation; cyanosis; disease association; Down syndrome; Fallot tetralogy; female; great vessels transposition; heart atrium septum defect; heart injury; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; human; infant; karyotype 46,XX; karyotype 47,XYY; karyotyping; major clinical study; male; newborn; Pakistan; patent ductus arteriosus; pulmonary valve atresia; retrospective study

Conjoined Twins Separation Leading to the Death of One Twin: An Expanded Ethical Analysis of Issues Facing the ICU Team - Cummings, B.M.; Paris, J.J. (Journal of Intensive Care Medicine, 2019)
A recent case of conjoined twins required multiple hospitalizations in the pediatric intensive care unit and led to a difficult situation confronting staff regarding the potential separation where surgery would result in the death of one twin. The hospital ethics committee was consulted. A systematic approach was utilized to examine medical standards, historical precedents, and various ethical and legal frameworks. The ethics committee believed that either proceeding with or forgoing attempted separation surgery would be ethically acceptable. We share our reasoning and lessons learned for others facing this situation in the future.
Keywords: antecedent variable; article; bladder function; case report; child; child hospitalization; circulation; clinical article; clinical decision making; conjoined twins; cyanotic heart disease; death; dietary intake; ethics; female; human; intestine function; medical assessment; mobilization; pediatric intensive care unit; pelvis; physical disease by anatomical structure; preschool child; priority journal; pulmonary valve atresia; quality of life; sternum; survival; tricuspid valve atresia

IMPACT Registry and National Pediatric Cardiology Quality Improvement Collaborative: Contributions to Quality in Congenital Heart Disease - Martin, G.R.; Anderson, J.B.; Vincent, R.N. (World Journal for Pediatric and Congenital Heart Surgery, 2019)
The IMproving Pediatric and Adult Congenital Treatments (IMPACT) Registry and the National Pediatric Cardiology Quality Improvement Collaborative (NPC-QIC) are two efforts initiated to improve outcomes in the congenital heart disease field. The IMPACT Registry is focused on evaluating the use, risks, adverse events (AEs), and outcomes associated with diagnostic and common interventional catheterization procedures in all children and adults with congenital heart disease. Utilizing a modular approach, the common procedures include diagnostic cardiac catheterization, atrial septal defect device closure, patent ductus arteriosus device closure, pulmonary valvuloplasty, aortic valvuloplasty, balloon and stent angioplasty of coarctation of the aorta, pulmonary artery balloon stent angioplasty, transcatheter pulmonary valve replacement, and electrophysiology procedures including radiofrequency ablation. To date, important observations on the common procedures have been made and a risk stratification methodology has been created to allow comparisons between centers in AEs and quality improvement activity. The registry is open to international participation. The NPC-QIC was developed to reduce mortality and improve the quality of life of infants with Hypoplastic Left Heart Syndrome (HLHS) during the interstage period between discharge from the Norwood operation and admission for the bidirectional Glenn procedure. Mortality in the interstage has been reduced by 44%. The IMPACT Registry and the NPC-QIC have demonstrated value to the congenital heart disease community. The IMPACT Registry, however, has not yet demonstrated an impact on patient outcomes. The NPC-QIC, which combines both a registry with a learning collaborative with specific aims, key drivers, and change strategies, has made more significant gains with reductions in variation, growth failures, and mortality.
Keywords: atrial septal occluder; aortic valve repair; article; blood clotting disorder; carotid artery stenting; congenital heart disease; electrophysiology; Glenn shunt; health care system; heart atrium septum defect; heart catheterization; human; hypoplastic left heart syndrome; mortality; patent ductus arteriosus; pediatric cardiology; percutaneous transluminal angioplasty; priority journal; pulmonary valve replacement; pulmonary valvuloplasty; quality of life; radiofrequency ablation; total quality management; treatment outcome

Impact of Congenital Cardiac Catheterization Project on Outcomes-Quality Improvement (C3PO-QI) in LMICs - Ali, F.; Qasim Mehdi, M.; Akhtar, S.; Aslam, N.; Abbas, R.; Shah, I.; Abidi, J.; Arthur, S.; Nizar, Z.; Goodmann, A.; Bergersen, L.; Hasan, B. (Heart Asia, 2019)
Background The importance of registries for collaborative quality improvement has been overlooked in low/middle-income countries (LMIC). Aga Khan University Hospital (AKUH) in Pakistan joined the Congenital Cardiac Catheterization Project on Outcomes-Quality Improvement (C3PO-QI) in March 2017 with the goal of leveraging international collaboration to improve patient care and institutional standards. Methods The C3PO-QI key driver-based approach was used, with certain modifications, for process re-engineering in AKUH's congenital cardiac catheterisation laboratory (CCL) to reduce radiation exposure during cardiac catheterisation procedures (the primary outcome of C3PO- QI). Educating staff and standardising procedural documentation were the principal goals of the process re-engineering. Data survey was used to assess staff knowledge, attitude and practice before and after the initiative. Additionally, case demographics and outcomes were compared between AKUH and C3PO-QI centres. Results There was an increase in appropriate recording of radiation surrogates (0%-100%, p=0.00) and in the percentage of cases that met the established benchmark of 'Ideal documentation' (35% vs 95%, p=0.001). There was also an increase in self-reported staff interest during the case (25% vs 75%, p=0.001). AKUH versus C3PO-QI data showed similar demographic characteristics. There was a slight over-representation of diagnostic cases (42% vs 32%) as compared with interventional (58% vs 68%) at AKUH. Furthermore, interventional procedures were predominately PDA and ASD device closures (n=19 and 15, respectively). The frequency of adverse events were the same between AKUH and collaborative sites. Conclusion Collaborative efforts between developed and LMIC CCL are significant in advancing system-level processes.
Keywords: cardiovascular stent; patent ductus arteriosus stent; adolescent; adverse event; aortic coarctation; aortic stenosis; aortic valve repair; article; atrioventricular septal defect; child; clinical laboratory; clinical outcome; clinical practice; comparative study; congenital heart disease; cross-sectional study; demography; descriptive research; female; fluoroscopy; great vessels transposition; health personnel attitude; heart arrhythmia; heart atrium septum defect; heart catheterization; heart hemodynamics; heart single ventricle; heart ventricle septum defect; hematoma; human; interventional cardiovascular procedure; low income country; major clinical study; male; medical documentation; medical staff; middle income country; patent ductus arteriosus; preschool child; priority journal; professional knowledge; pulmonary valve atresia; pulmonary valve stenosis; pulmonary valvuloplasty; radiation dose distribution; radiation exposure; radiation hazard; radiation protection; sedation; self report; staff training; standardization; stent thrombosis; teaching hospital; total quality management

Initiating a Fontan multidisciplinary clinic: Decreasing care variability, improving surveillance, and subsequent treatment of Fontan survivors - Di Maria, M.V.; Barrett, C.; Rafferty, C.; Wolfe, K.; Kelly, S.L.; Liptzin, D.R.; Brigham, D.; Younoszai, A. (Congenital Heart Disease, 2019)
Background: Children with single ventricle (SV) heart disease who undergo Fontan operation are at risk for developing multiorgan dysfunction. Although survival has improved, significant comorbidities involving multiple organ systems may develop, requiring evaluation and management by many subspecialists. Using data from an internal survey, we documented high care variability for our Fontan population. We then developed a multidisciplinary clinic, designed and implemented a clinical care pathway to decrease variability of patient assessment. Methods: After creating a multidisciplinary team and a clinical care pathway, we initiated a multidisciplinary clinic (MDC) where patients could see multiple subspecialists during a single encounter. We then monitored our effectiveness by retrospective chart review to determine care pathway adherence (process measure) and incidence of new diagnoses of end-organ injury (outcome measure) as well interventions implemented. Adherence was analyzed using statistical process control (SPC) charts. Results: Eighty-six patients were seen in the MDC from January 2016 to September 2017. The proportion of patients with appropriate testing increased, related to strong care pathway adherence. A significant amount of novel pathology was diagnosed in all evaluated organ systems, both Fontan-associated comorbidities and general pediatric diagnoses. Subsequent interventions included cardiac catheterization n = 21 (31%) with more than half of these patients undergoing intervention n = 17 (20%), and liver biopsy n = 9 (10%). Additionally, 58 patients (67%) were referred to a neuropsychologist based on perceived clinical need, with n = 34 (40%) undergoing a neuropsychological evaluation. Conclusions: Children who have undergone Fontan palliation are at risk for developing cardiac and noncardiac comorbidities. Use and adherence to an institutional care pathway resulted in the diagnosis of significant novel pathology and subsequently provided opportunity for intervention.
Keywords: adolescent; adult; article; child; clinical pathway; comorbidity; female; Fontan procedure; heart catheterization; heart single ventricle; human; liver biopsy; major clinical study; male; multidisciplinary team; neuropsychological test; outcome assessment; patient assessment; priority journal; protocol compliance; survivor; young adult

Oxygen availability in respiratory muscles during exercise in children following fontan operation - Stöcker, F.; Neidenbach, R.; Fritz, C.; Oberhoffer, R.M.; Ewert, P.; Hager, A.; Nagdyman, N. (Frontiers in Pediatrics, 2019)
Introduction: As survival of previously considered as lethal congenital heart disease forms is the case in our days, issues regarding quality of life including sport and daily activities emerge. In patients with Fontan circulation, there is no pump to propel blood into the pulmonary arteries since the systemic veins are directly connected to the pulmonary arteries. The complex hemodynamics of Fontan circulation include atrial function, peripheral muscle pump, integrity of the atrioventricular valve, absence of restrictive, or obstructive pulmonary lung function. Therefore, thoracic mechanics are of particular importance within the complex hemodynamics of Fontan circulation. Methods: To understand the physiology of respiratory muscles, the aim of this study was to examine the matching of auxiliary respiratory muscle oxygen delivery and utilization during incremental exercise in young male Fontan patients (n = 22, age = 12.04 ± 2.51) and healthy Controls (n = 10, age = 14.90 ± 2.23). All subjects underwent a cardiopulmonary exercise test (CPET) to exhaustion whereas respiratory muscle oxygenation was measured non-invasively using a near-infrared spectrometer (NIRS). Results: CPET revealed significantly lower peak power output, oxygen uptake and breath activity in Fontan patients. The onset of respiratory muscle deoxygenation was significantly earlier. The matching of local muscle perfusion to oxygen demand was significantly worse in Fontans between 50 and 90% V.O2peak. Findings: The results indicate that (a) there is high strain on respiratory muscles during incremental cycling exercise and (b) auxiliary respiratory muscles are worse perfused in patients who underwent a Fontan procedure compared to healthy Controls. This might be indicative of a more general skeletal muscle strain and worse perfusion in Fontan patients rather than a localized-limited to thoracic muscles phenomenon.
Keywords: oxygen; adolescent; adult; article; body surface; breathing muscle; cardiopulmonary exercise test; child; clinical article; deoxygenation; exercise; exercise intensity; exhaustion; female; Fontan procedure; heart rate; human; male; muscle perfusion; near infrared spectroscopy; oxygen consumption; oxygenation; pediatric surgery; post hoc analysis; skinfold thickness

Outcomes and factors associated with early mortality in pediatric and neonatal patients requiring extracorporeal membrane oxygenation for heart and lung failure - Azizov, F.; Merkle, J.; Fatullayev, J.; Eghbalzadeh, K.; Djordjevic, I.; Weber, C.; Saenko, S.; Kroener, A.; Zeriouh, M.; Sabashnikov, A.; Bennink, G.; Wahlers, T. (Journal of Thoracic Disease, 2019)
Background: Mortality and morbidity after surgical repair for complex congenital heart defects and severe cardiopulmonary failure on extracorporeal membrane oxygenation (ECMO) support remain high despite significant advances in medical management and technological improvements. We report on outcomes and factors after using ECMO in our surgical pediatric population including short- and long-term survival. Methods: A total of 45 neonatal and pediatric patients were identified who needed ECMO in our department between January 2008 and December 2016. In 41 cases (91%) a vaECMO (ECLS) was implemented, whereas 4 patients (9%) received vvECMO treatment for respiratory failure. In 33 cases vaECMO was implanted following cardiac surgery for congenital heart disease (CHD), whereas in 8 patients ECMO was utilized by means of extracorporeal cardiopulmonary resuscitation (eCPR) following refractory cardiac arrest. The primary endpoint of the present study was survival to discharge and long-term survival free from neurological impairments. Univariate and bivariate analysis was performed to address predictors for outcome. Kaplan-Meier survival analysis was used to address mid- and long-term survival. Results: Median [IQR] duration of ECMO support was 3 [2, 5] days (range, 1–17 days). Median age at ECMO implantation was 128 [14, 1,813] days, median weight of patients was 5.4 [3.3, 12] kg. Totally 10 patients included in this study were diagnosed with concomitant genetic conditions. A total of 20 (44%) patients were successfully weaned off ECMO (survived >24 h after ECMO explantation), whereas 15 (33%) of them survived to discharge. Single ventricle (SV) repair was performed in 14, biventricular repair in 19 patients. Neonates (<30 days of age), female patients, patients with genetic conditions, SV repair patients, and eCPR patient cohort showed lower odds of survival on ECMO. Failed myocardial recovery (P=0.001), profound circulatory failure despite a high dose of catecholamines (P<0.001), neurological impairment pre-ECMO and post-ECMO (P=0.04 and P<0.001, respectively), and severe pulmonary failure despite high respiratory pressure settings were most common mortality reasons. Conclusions: ECMO provides efficient therapy opportunities for life-threatening conditions. Nevertheless, neonates and pediatric patients who underwent ECMO were at high risk for cerebrovascular events and poor survival. Appropriate patient selection using predictors of outcome reducing complications might improve outcomes of this patient cohort.
Keywords: activated partial thromboplastin time; arterial switch operation; article; bivariate analysis; child; childhood mortality; clinical article; computer assisted tomography; creatinine clearance; disease association; elective surgery; electroencephalography; electronic medical record; extracorporeal oxygenation; female; glomerulus filtration rate; heart arrest; heart failure; heart single ventricle; heart surgery; hospital mortality; human; infant; long term survival; lung insufficiency; male; neonatal intensive care unit; newborn; newborn mortality; outcome assessment; patient selection; pediatric intensive care unit; pediatric patient; platelet count; postoperative complication; postoperative period; practice guideline; prothrombin time; quality of life; respiratory failure; resuscitation; survival analysis; urea nitrogen blood level

Paediatric donation after circulatory determined death heart transplantation using donor normothermic regional perfusion and ex situ heart perfusion: A case report - Khushnood, A.; Butt, T.A.; Jungschleger, J.; Henderson, P.; Smith, J.H.; De Rita, F.; Nassar, M.; Page, A.; Messer, S.; Large, S.; Dark, J.H.; Parry, G.; et al. (Pediatric Transplantation, 2019)
This is a report of a unique DCD paediatric heart transplant whereby normothermic regional perfusion was used to assess DCD heart function after death followed by ex situ heart perfusion of the graft during transportation from donor to recipient hospitals. The DCD donor was a 9-year-old boy weighing 84 kg. The recipient was 7-year-old boy with failing Fontan circulation and weighed 23 kg. It was an ABO-compatible heart transplantation. The DCD heart was reperfused and assessed using normothermic regional perfusion followed by portable ex situ heart perfusion during transportation. The orthotopic heart transplantation was successful with good graft function and no evidence of rejection on endomyocardial biopsy at 30 days post-transplant. At 1-year follow-up, excellent graft function is maintained, and he is attending school with a good quality of life. DCD heart transplantation in children is a promising solution to reducing paediatric waiting times. The case demonstrates the feasibility of using normothermic regional perfusion in the donor and ex situ heart perfusion during graft transportation. This combination allowed a functional assessment whilst minimizing warm ischaemia resulting in a successful outcome. More research and long-term follow-up are needed in order to benefit from the huge potential that paediatric DCD heart transplantation has to offer.
Keywords: azathioprine; cyclosporine; dipeptidyl carboxypeptidase inhibitor; methylprednisolone; sildenafil; thymocyte antibody; aortic valve disease; article; case report; child; clinical article; donation after circulatory determined death; follow up; graft recipient; heart donor; heart function; heart perfusion; heart transplantation; human; human tissue; hypoplastic left heart syndrome; immunosuppressive treatment; length of stay; male; mitral valve atresia; operation duration; pediatrics; school child; surgical technique; treatment outcome; treatment response

Spectrum of Cardiovascular Abnormalities in Infants Born to Diabetic Mother in a Tertiary Care Center - Arul, A.S.; Babu Kandha Kumar, A.S.; Kiruthiga, K.; Priya, M.K.; Neveythaa, S.A. (Indian Journal of Cardiovascular Disease in Women - WINCARS, 2019)
Background Diabetes mellitus is one of the most common medical problems among pregnant women. Now, gestational diabetes mellitus (GDM) is increasing and amounts to 17% in Asian women but only in 4% of American and European women. In southern India, the prevalence of GDM is 17% in urban women, 13.8% in semiurban, and 9.8% in rural women. Aim The aim of the study is to find the cardiovascular abnormalities in infants born to a diabetic mother (IDM) and the association between infant's heart lesion and diabetes mellitus in pregnant mother in a tertiary care center. Materials and Methods All babies born to both pregestational and gestational diabetic mother were included. Information regarding maternal type of diabetes, treatment regimen, maternal glycemic control status, antenatal ultrasonogram, baby's sex, birth weight, gestational age, and clinical features were collected. Echocardiogram was done for all the babies. Results Out of the 100 IDM, 28 babies had cardiac disease, 5 babies had cyanotic heart disease, and 23 babies had acyanotic heart disease. Out of 100 diabetic mothers, 66 were on meal plan, 21 were on oral hypoglycemic agent (OHA) metformin, and 13 were on insulin therapy. Among 66 babies whose mother was on the meal plan, 8 had cardiac abnormality. Among the 21 mothers on OHA, 7 babies had cardiac abnormality and all the 13 babies of mothers who were on insulin had cardiac abnormality which was a significant finding among the IDM. Conclusion Maternal diabetes is a significant risk factor for heart disease in the newborn. Careful evaluation and early diagnosis of heart diseases in this high-risk group is of great value. Both pregestational and gestational diabetic mothers should monitor their blood sugar and maintain it in a normal range at the time of conception and early in pregnancy to reduce the risk of congenital heart disease in IDM.
Keywords: insulin; metformin; oral antidiabetic agent; arterial trunk; article; asymmetrical septal hypertrophy; birth weight; cardiovascular malformation; clinical feature; congenital heart disease; cyanotic heart disease; diabetic diet; early diagnosis; echocardiography; female; gestational age; glucose blood level; glycemic control; great vessels transposition; heart atrium septum defect; heart murmur; heart ventricle septum defect; high risk infant; human; hypoplastic left heart syndrome; infant; insulin treatment; large for gestational age; major clinical study; male; maternal diabetes mellitus; neonatal intensive care unit; newborn; patent ductus arteriosus; patent foramen ovale; priority journal; risk factor; risk reduction; small for date infant; tertiary care center; treatment outcome; tricuspid valve atresia

ECMO is in the air: Long distance air/ground transport of a child on extra corporeal membrane oxygenation - Assy, J.; Fawzi, I.; Arabi, M.; Bulbul, Z.; Bitar, F.; Majdalani, M.; Sharara, R.; El Rassi, I. (Egyptian Journal of Critical Care Medicine, 2018)
Background: Extracorporeal membrane oxygenation (ECMO) is a temporary mechanical support system that handles the function of the heart and/or lungs in patients with a variety of cardiac and respiratory problems. Veno-arterial ECMO is most commonly used for patients recovering from heart surgery, suffering from cardiac shock, or awaiting a heart transplant. Case report: A 7 year old boy with a single ventricle physiology was admitted for a Fontan procedure with repair of the common valve. At the end of surgery, transesophagal echocardiography showed a severely depressed myocardial function, and weaning of bypass required a high inotropic support. During the following week, the heart never recovered, with an ejection fraction at 24%. Veno-Arterial ECMO was decided on postoperative day 9 with a 19 Fr venous cannula inserted through the right jugular vein into the intracardiac Fontan baffle, and a 15 Fr arterial cannula into the right carotid artery. On ECMO day 7, after failure to wean from ECMO, he was listed for an urgent heart transplant, with the suggestion of a transfer to Europe, for a shorter transplantation delay. The ECMO team from Hamad Hospital in Qatar accomplished the transfer successfully, on a humanitarian basis. The transfer was done on ECMO Day 10. The child was safely admitted to a hospital in Belgium, and listed again for an urgent heart transplant. Conclusion: With an experienced team, and the proper equipment, on-ECMO air transport of critical patients over thousands of kilometers is today safely feasible.
Keywords: arterial cannula; left ventricular assist device; epinephrine; inotropic agent; levosimendan; milrinone; noradrenalin; aircraft; ambulance; article; Belgium; Blalock Taussig shunt; case report; child; clinical article; disease severity; extracorporeal oxygenation; Fontan procedure; forward heart failure; Glenn shunt; heart catheterization; heart transplantation; heart valve replacement; heart ventricle septum defect; helicopter; hospital admission; human; inotropism; Lebanon; low drug dose; male; patient history of surgery; patient transport; pediatric intensive care unit; preoperative evaluation; Qatar; school child; transesophageal echocardiography

Neurobehavioral evaluation of neonates with congenital heart disease: a cohort study - Hogan, W.J.; Winter, S.; Pinto, N.M.; Weng, C.; Sheng, X.; Conradt, E.; Wood, J.; Puchalski, M.D.; Tani, L.Y.; Miller, T.A. (Developmental Medicine and Child Neurology, 2018)
Aim: To describe neurobehavioral patterns in neonates with congenital heart disease (CHD). Method: A cohort study describing neurobehavioral performance of neonates with CHD requiring cardiac surgery. The neonates were evaluated preoperatively and postoperatively with the Neonatal Intensive Care Unit Network Neurobehavioral Scale (NNNS) and scores were compared with published normative values. Clinical factors were obtained by chart review to assess their association with behavior. The CHD NNNS score pattern was compared with previously reported profiles in other high-risk populations. Results: NNNS evaluations were completed on 67 neonates with CHD, resulting in 97 evaluations (50 preoperative, 47 postoperative). Compared with normative values, the cohort with CHD demonstrated decreased attention, regulation, asymmetry, stress, arousal, and excitability, along with increased non-optimal reflexes, lethargy, and need for handling (p<0.05 for all). Additional clinical factors had a minimal effect on the neurobehavioral pattern. Compared with previously published patterns in high-risk neonates without CHD, the cohort with CHD demonstrated a unique pattern of behavior. Interpretation: Neonates with CHD demonstrate different neurobehavioral performance compared with typically developing neonates born at term as well as other high-risk neonates. Our experience suggests there is a unique neonatal neurobehavioral pattern in the hospitalized population with CHD. Targeted neonatal neurobehavioral evaluations may be useful in developing specific therapies to improve neurodevelopmental outcomes in neonates with CHD. What this paper adds: Neonates with congenital heart disease demonstrate different neurobehavioral performance than typically developing neonates. Evaluation of neonatal neurobehavioral performance provides an opportunity to identify neurodevelopmental variability early. Identification of neurobehavioral performance variability allows targeted interactions and therapy.
Keywords: aortopulmonary septal defect; arousal; article; attention; behavior disorder; cardiopulmonary bypass; cohort analysis; congenital heart disease; excitability; Fallot tetralogy; female; genetic disorder; great vessels transposition; habituation; heart catheterization; heart left right shunt; heart surgery; high risk population; human; hypoplastic left heart syndrome; lethargy; major clinical study; male; medical record review; neonatal abstinence syndrome; neonatal intensive care unit; nerve cell differentiation; newborn; premature labor; prenatal diagnosis; priority journal; pulmonary valve atresia; retrospective study; physiological stress; tricuspid valve atresia

Perioperative Cerebral Oxygenation Metabolism in Neonates with Hypoplastic Left Heart Syndrome or Transposition of the Great Arteries - Neunhoeffer, F.; Hofbeck, M.; Schlensak, C.; Schuhmann, M.U.; Michel, J. (Pediatric Cardiology, 2018)
Optimizing oxygen delivery to the brain is one of the main goals in children with congenital heart defects after surgery. It has been shown that cerebral oxygen saturation (cSO2) is depressed within the first day after neonatal cardiopulmonary bypass surgery. However, peri-operative cerebral oxygen metabolism has not yet been assessed in previous studies. The aim of this study was to describe the peri-operative changes in cerebral oxygen metabolism in neonates with congenital heart defects following cardiopulmonary bypass surgery. Prospective observational cohort study. PICU of a tertiary referral center. Fourteen neonates with hypoplastic left heart syndrome (HLHS) undergoing Norwood procedure and 14 neonates with transposition of great arteries (TGA) undergoing arterial switch operation (ASO) were enrolled. Pediatric heart surgery. We measured non-invasively regional cSO2 and microperfusion (rcFlow) using tissue spectrometry and laser Doppler flowmetry before and after surgery. Cerebral fractional tissue oxygen extraction (cFTOE), the arterio–cerebral difference in oxygen content (acDO2) and approximated cerebral metabolic rate of oxygen (aCMRO2) were calculated. According to the postsurgical hemodynamics, arterial saturation (aSO2) normalized immediately after surgery in the TGA group, whereas HLHS patients still were cyanotic. cSO2 significantly increased in TGA group over 48 h after ASO (p = 0.004) and was significantly higher compared to HLHS group after Norwood procedure. cFTOE as a risk marker for brain injury was elevated before surgery (TGA group 0.37 ± 0.10, HLHS group 0.42 ± 0.12) and showed a slight decrease after ASO (p = 0.35) but significantly decreased in patients after Norwood procedure (p = 0.02). Preo-peratively, acDO2 was significantly higher in patients with HLHS compared to patients with TGA (7.7 ± 2.5 vs. 5.2 ± 1.6 ml/dl, p = 0.005), but normalized in the posto-perative course. Before surgery, the aCMRO2 was slightly higher in the HLHS group (5.1 ± 1.5 vs. 3.9 ± 2.5 AU, p = 0.14), but significantly decreased after Norwood procedure (− 1.6 AU, p = 0.009). There was no difference in rcFlow between both groups and between the points in time prior and after surgery. Neonates undergoing cardiac surgery suffer from peri-operative changes in hemodynamics and cerebral hypoxemic stress. The cerebral oxygen metabolism seems to be more affected in cyanotic children with functionally univentricular hearts compared to post-operative acyanotic patients. Additional stress factors must be avoided to achieve the best possible neurological outcome.
Keywords: arterial switch operation; arterio cerebral difference in oxygen content; article; brain injury; brain oxygen consumption; cardiopulmonary bypass; cerebral metabolic rate of oxygen; cerebral oxygen saturation; clinical article; cohort analysis; controlled study; Doppler flowmetry; female; great vessels transposition; hemodynamics; human; hypoplastic left heart syndrome; male; nervous system parameters; newborn; Norwood procedure; observational study; oxygen extraction fraction; oxygen saturation; perioperative period; prospective study; risk factor; spectroscopy

Psychosocial functioning of parents of children with heart disease—describing the landscape - Wray, J.; Cassedy, A.; Ernst, M.M.; Franklin, R.C.; Brown, K.; Marino, B.S. (European Journal of Pediatrics, 2018)
The aim was to describe the psychological functioning of parents of school-age children with heart disease (HD) in a large-scale, transnational evaluation of parent dyads across the spectrum of cardiac diagnoses and a range of psychosocial domains. Parents of children with HD attending routine out-patient cardiology follow-up visits completed questionnaires assessing their mental health, coping, and family functioning. Parents (1197 mothers and 1053 fathers) of 1214 children (mean age: 12.6 years; S.D. 3.0 years; median time since last surgery: 8.9 years) with congenital or acquired HD from three centers each in the UK and the USA participated (80% response rate). Parents of children with milder HD demonstrated few differences from healthy norms and had significantly lower scores on measures of illness-related stress and post-traumatic stress than parents of children with single ventricle conditions or cardiomyopathy. Parents in these latter two diagnostic sub-groups had significantly higher levels of anxiety and depression than healthy norms but did not differ on other measures of family functioning and coping skills. There were few differences between parents from the UK and the USA. Agreement between mothers and fathers within a dyad was highest for the measure of frequency of illness-related stressors (ICC = 0.67) and lowest for anxiety (ICC = 0.12). Conclusion: Our results suggest two different pathways for the long-term psychological well-being of parents of children with HD: on the one hand, more complex HD is associated with poorer long-term psychosocial outcomes; in contrast, there are also grounds for optimism, particularly for parents of children with less complex conditions, with better psychological outcomes noted for some groups of parents compared to previously reported early psychosocial outcomes. Future work needs to identify factors other than disease severity which might explain poorer (or better) functioning in some parents of children with more complex HD.What is Known:• Parents of children with congenital heart disease report elevated levels of anxiety, depression, and stress after cardiac surgery in infancy.• Maternal mental health problems can have an adverse impact on the psychological adjustment of the child with congenital heart disease.What is New:• Parents of children with milder forms of heart disease do not differ from healthy norms in the longer term and psychological outcomes are better than might be expected from early findings.• More complex diagnoses, particularly functional single ventricle conditions and cardiomyopathy, are associated with poorer long-term psychosocial outcomes for parents.
Keywords: adolescent; adult; anxiety; article; cardiomyopathy; child; coping behavior; cross-sectional study; depression; disease severity; family functioning; father; female; heart disease; heart single ventricle; human; major clinical study; male; mental health; mother; parent; parental stress; posttraumatic stress disorder; priority journal; questionnaire; social psychology; United Kingdom; United States

Single-centre experience in stenting arterial shunts for adult CHD patients with single-ventricle physiology and pulmonary blood flow dependent on arterial shunts - Kasem, M.; Bentham, J.; Thomson, J. (Cardiology in the Young, 2018)
Objectives The objectives of this study were to describe the approach to stenting arterial shunts in adult congenital patients with single-ventricle physiology and to assess the medium-term clinical and haemodynamic outcomes following stent insertion. Background Adult patients with single-ventricle physiology and pulmonary blood flow dependent on a surgically placed arterial shunt who did not progress to venous palliation are extremely challenging to manage. Progressive cyanosis secondary to narrowing of the shunt has a marked impact on exercise tolerance and results in intolerable well-being for these patients. Stenting arterial shunts in adult patients is one method that can help improve pulmonary blood flow. There is very limited information in the literature about this patient. Methods: This is a retrospective study for arterial shunts stenting conducted between 2008 and 2016. The peripheral oxygen saturations, the NYHA status, the haemoglobin, and the degree of atrio-ventricular valve regurgitation as assessed on transthoracic echo were compared before and 6-12 months after procedures. Results: There was a short-term improvement in oxygen saturations; the pre-procedure mean was 75.8 (SD 2.55)% (range 70-85%) and post-procedure mean was 83 (SD 2.52)% (range 78-87%), with a p value of 0.04. Haemoglobin level decreased from a pre-procedure mean of 22.06-20.28 g/L 6 months post procedure (range 18.1-24.4 to 13-23.3 g/L), with a p value of 0.44. NYHA class decreased from a mean of 3.2-2.2 post procedure. Left atrial volume for four of the cases did not change (22.6-76.6 ml [mean 48.4 ml] to 29.6-72.9 ml [mean 52 ml], p value: 0.83). Conclusions: Stenting stenotic arterial shunts is a useful method to gain a medium-term improvement on the oxygen saturation and clinical symptoms, and may act as a useful intermediate step for further management plans.
Keywords: arterial stent; biliary stent; coronary stent; everolimus eluting coronary stent; Genesis; polytetrafluoroethylene; hemoglobin; adolescent; adult; aortopulmonary shunt; arterial embolization; artery occlusion; article; Blalock Taussig shunt; clinical article; clinical outcome; congenital heart disease; cyanosis; disease severity; exercise tolerance; female; heart single ventricle; heart valve regurgitation; hemodynamics; hemoglobin blood level; human; lung blood flow; male; middle aged; New York Heart Association class; oxygen saturation; retrospective study; surgical approach; transthoracic echocardiography; Genesis; Gore-Tex; Multi-Link Ultra; Visi-pro; Xience

Safety of outpatient cardiac catheterisation in infants with single-ventricle or shunt-dependent biventricular congenital heart disease - Colombo, J.N.; Spaeder, M.C.; Hainstock, M.R. (Cardiology in the Young, 2018)
Objective: We aimed to investigate the incidence and causes of readmission of infants with single-ventricle and shunt-dependent biventricular CHD following routine, outpatient cardiac catheterisation.Background Cardiac catheterisation is commonly performed in patients with single-ventricle and shunt-dependent biventricular CHD for haemodynamic assessment and surgical planning. Best practices for post-procedural care in this population are unknown, and substantial variation exists between centres. Outpatient catheterisation reduces parental anxiety and decreases cost. Our institutional strategy is to discharge patients following a 4- to 6-hour post-procedure observation period. Methods: Retrospective cohort study using the Society of Thoracic Surgeons Database identified patients <1 year of age with pre-stage II single-ventricle CHD or shunt-dependent biventricular CHD who underwent cardiac catheterisation between 2007 and 2015. Readmission was defined as admission to the hospital within 48 hours after discharge after catheterisation. Results: A total of 92 patients were included in the analysis. Among them, 62 patients (67%) were discharged after a 4- to 6-hour observation period with only 3% readmission, 18 patients (20%) stayed for a 23-hour observation period, and 12 patients (13%) were admitted for >23 hours. There were no differences in baseline characteristics between discharged and admitted patients. Patients who underwent intervention were more likely to be admitted. Patients with hypoplastic left heart syndrome did not have major adverse events or readmissions. No intra- or peri-procedural deaths occurred. Conclusions: Outpatient cardiac catheterisation may be a safe option for infants with single-ventricle and shunt-dependent biventricular CHD, with low readmission rates and minimal morbidity.
Keywords: article; child care; cohort analysis; congenital heart disease; controlled study; disease severity; female; heart catheterization; heart hemodynamics; heart septum defect; heart single ventricle; high risk patient; hospital discharge; hospital readmission; human; hypoplastic left heart syndrome; infant; major clinical study; male; morbidity; outcome assessment; outpatient care; patient safety; retrospective study; treatment planning

Ventricular mechanics in adolescent and adult patients with a Fontan circulation: Relation to geometry and wall stress - Rösner, A.; Khalapyan, T.; Pedrosa, J.; Dalen, H.; McElhinney, D.B.; Friedberg, M.K.; Lui, G.K. (Echocardiography, 2018)
Background: Patients with single ventricle physiology and Fontan circulation are at increased risk for late complications and reduced survival. The aim of the study was to investigate the correlation between ventricular geometry and systolic regional function in different underlying anatomic conditions in adolescent and adult Fontan-palliated patients. Method: In a retrospective cross-sectional study, we measured 2D strain, ventricular diameters, ventricular volumes, ejection fraction (EF), global and segmental wall stress, and sphericity index. The same analyses were performed in 99 age- and gender-matched healthy individuals. Results: One hundred and one patients were included at a mean age of 21 (range 14–59) years. In comparison with healthy subjects, patients with Fontan circulation displayed larger ventricular volumes (153 ± 78 mL vs 116 ± 38 mL P < 0.05), reduced EF (43% ± 15% vs 55% ± 8% P < 0.05), reduced longitudinal (−13% ± 6% vs −21% ± 4% P < 0.05) and circumferential strain values (−15% ± 7% vs −22% ± 4% P < 0.05). Functionally single ventricles were more spherical (ratio of longitudinal to short-axis diameters 1.3 ± 0.3 vs 1.7 ± 0.2 P < 0.05). Circumferential strain correlated well with global wall stress and the degree of sphericity (R2 = 0.320), while segmental strain did not correlate with segmental wall stress. The percentage of segments with akinesia was relatively high (16 ± 16% vs 0 ± 0% P < 0.05) indicating reduced segmental contractile function. Conclusion: Functionally single ventricles after Fontan palliation have significantly reduced systolic regional and global function with a high intersegmental inhomogeneity. The underlying pathological mechanisms might be multifactorial, including ventricular geometry, sphericity, and regional contractile properties. Future studies are needed to investigate the role of ventricular geometry for clinical performance and outcome.
Keywords: adolescent; adult; akinesia; article; coronary artery blood flow; correlational study; cross-sectional study; female; Fontan procedure; geometry; heart ejection fraction; heart ventricle contractility; heart ventricle function; heart ventricle volume; human; major clinical study; male; palliative therapy; priority journal; retrospective study; speckle tracking echocardiography; systolic blood pressure

Psychosocial functioning of parents of children with heart disease-describing the landscape - Wray, J.; Cassedy, A.; Ernst, M.M.; Franklin, R.C.; Brown, K.; Marino, B.S. (European journal of pediatrics, 2018)
The aim was to describe the psychological functioning of parents of school-age children with heart disease (HD) in a large-scale, transnational evaluation of parent dyads across the spectrum of cardiac diagnoses and a range of psychosocial domains. Parents of children with HD attending routine out-patient cardiology follow-up visits completed questionnaires assessing their mental health, coping, and family functioning. Parents (1197 mothers and 1053 fathers) of 1214 children (mean age: 12.6 years; S.D. 3.0 years; median time since last surgery: 8.9 years) with congenital or acquired HD from three centers each in the UK and the USA participated (80% response rate). Parents of children with milder HD demonstrated few differences from healthy norms and had significantly lower scores on measures of illness-related stress and post-traumatic stress than parents of children with single ventricle conditions or cardiomyopathy. Parents in these latter two diagnostic sub-groups had significantly higher levels of anxiety and depression than healthy norms but did not differ on other measures of family functioning and coping skills. There were few differences between parents from the UK and the USA. Agreement between mothers and fathers within a dyad was highest for the measure of frequency of illness-related stressors (ICC = 0.67) and lowest for anxiety (ICC = 0.12).Conclusion: Our results suggest two different pathways for the long-term psychological well-being of parents of children with HD: on the one hand, more complex HD is associated with poorer long-term psychosocial outcomes; in contrast, there are also grounds for optimism, particularly for parents of children with less complex conditions, with better psychological outcomes noted for some groups of parents compared to previously reported early psychosocial outcomes. Future work needs to identify factors other than disease severity which might explain poorer (or better) functioning in some parents of children with more complex HD. What is Known: • Parents of children with congenital heart disease report elevated levels of anxiety, depression, and stress after cardiac surgery in infancy. • Maternal mental health problems can have an adverse impact on the psychological adjustment of the child with congenital heart disease. What is New: • Parents of children with milder forms of heart disease do not differ from healthy norms in the longer term and psychological outcomes are better than might be expected from early findings. • More complex diagnoses, particularly functional single ventricle conditions and cardiomyopathy, are associated with poorer long-term psychosocial outcomes for parents.
Keywords: adolescent; adult; child; child parent relation; clinical trial; coping behavior; cross-sectional study; female; heart disease; human; male; mental disease; mental stress; middle aged; multicenter study; preschool child; psychology; questionnaire; United Kingdom; United States

Parents' experiences of receiving an antenatal versus postnatal diagnosis of complex congenital heart disease - Reid, A.; Gaskin, K. (Nursing children and young people, 2018)
BACKGROUND: The time point at which parents receive a diagnosis of congenital heart disease (CHD) has changed over the years due in part to advances in fetal ultrasound. However, CHD remains undiscovered until after birth in some cases. The psychological effect of time of diagnosis on parents' experiences has not been well researched. AIM: To explore parents' experiences at the time of diagnosis of complex CHD and to compare if experiences differ when receiving an antenatal versus postnatal diagnosis. METHOD: Descriptive and thematic analysis of primary mixed qualitative and quantitative data, collected in 2012-2013, from an online survey of parents ( n =22) whose infants had undergone stage one surgery for a functionally univentricular heart. FINDINGS: Four themes emerged: parents' understanding of the condition at the time of diagnosis; parents' emotions at the time of diagnosis; sources of support at the time of diagnosis; and additional sources of information after the diagnosis. CONCLUSION: There are implications for practice in terms of who provides the diagnosis and, more importantly, how well it is explained. Professionals need to assess parents' emotional status, information needs and level of understanding irrespective of time of diagnosis, so that support is individualised, sensitive and time appropriate.
Keywords: adult; child parent relation; congenital heart malformation; echography; female; human; infant; life event; male; middle aged; newborn; pregnancy; prenatal diagnosis; preschool child; procedures; psychology; qualitative research; questionnaire; time factor; United Kingdom

Recognition of Neonatal Lymphatic Flow Disorder: Fetal MR Findings and Postnatal MR Lymphangiogram Correlation - Biko, D.M.; Johnstone, J.A.; Dori, Y.; Victoria, T.; Oliver, E.R.; Itkin, M. (Academic Radiology, 2018)
Rationale and Objectives: This study aimed to describe prenatal and postnatal imaging features and outcomes of neonates with neonatal lymphatic disorders (NLDs). Materials and Methods: An institutional review board-approved search of the radiology database for patients with NLD identified five patients. Inclusion criteria include prenatal imaging (fetal magnetic resonance [MR] imaging and ultrasound) and postnatal three-dimensional T2 Sampling Perfection with Application optimized Contrasts using different flip angle Evolution (SPACE) and dynamic contrast-enhanced MR lymphangiography within 6 months of life. Chart review was undertaken to evaluate morbidity and mortality. Results: Prenatal finding of “nutmeg lung” or fetal pulmonary lymphatic disorder was identified in all five patients on fetal MR imaging, and in four of five patients on fetal ultrasound. Postnatal dynamic contrast-enhanced MR lymphangiography demonstrated abnormal lymphatic flow to the lungs in four of five patients, but absent in the single patient with coexisting hypoplastic left heart syndrome (HLHS). Dermal backflow was seen in one patient, also the only patient with prenatal body wall edema. Three patients with lymphatic flow to the lungs only were classified as neonatal chylothorax. The patient with dermal backflow and perfusion to the lungs was diagnosed with central lymphatic flow disorder (CLFD). The HLHS patient with normal lymphatic perfusion maintained the HLHS diagnosis. Of the five patients, the patient with CLFD and the one with HLHS expired because of respiratory distress. Conclusions: NLDs can be recognized on prenatal and postnatal imaging and may be primary, as in neonatal chylothorax or CLFD, or secondary. In this small series, “nutmeg lung” was present in all patients. Prenatal imaging demonstrates that body wall edema may correlate with postnatal dermal backflow, which, in our small cohort, carried a poor prognosis.
Keywords: nuclear magnetic resonance scanner; gadobutrol; iodinated poppyseed oil; article; central lymphatic flow disorder; chylothorax; clinical article; conservative treatment; contrast enhancement; fetus echography; health care; human; hypoplastic left heart syndrome; lung lymph flow; lymphangiography; lymphatic flow disorder; lymphatic system disease; newborn; newborn disease; nuclear magnetic resonance imaging; perinatal period; pleura effusion; prenatal diagnosis; priority journal; respiratory distress; retrospective study; gadavist; lipiodol

Executive Function and Psychosocial Quality of Life in School Age Children with Congenital Heart Disease - Sanz, J.H.; Wang, J.; Berl, M.M.; Armour, A.C.; Cheng, Y.I.; Donofrio, M.T. (Journal of Pediatrics, 2018)
Objective: To test a model to predict psychosocial quality of life (QOL) in children with congenital heart disease (CHD) via executive dysfunction. Study design: Parents of 91 children with CHD requiring surgery in the first year of life completed questionnaires by mail or as part of their cardiology clinic visit. Latent class analysis identified 2 groups of patients with different likelihoods of executive dysfunction. Select medical and demographic characteristics and executive dysfunction group membership were evaluated as predictors of QOL using structural equation modeling. Results: In children with CHD, aortic obstruction, male sex, and premature birth predicted worse executive function, explaining 59% of the variance. Structural equation modeling results indicated that executive dysfunction plays an important mediating role, through which CHD with aortic obstruction, male sex, and premature birth indirectly affect psychosocial QOL. Neurologic abnormalities and single-ventricle CHD did not significantly predict executive dysfunction or QOL. Conclusions: Executive dysfunction is a strong predictor of psychosocial QOL at school age. Select medical and demographic risk factors did not directly predict QOL at school age in CHD; however, aortic obstruction, premature birth, and male sex impacted QOL indirectly by contributing to executive dysfunction. These findings suggest important risk factors for executive dysfunction that can be monitored, allowing for provision of early supports for executive skills development in an effort to improve long term psychosocial QOL in at-risk children with CHD.
Keywords: adolescent; aortic occlusion; article; child; congenital heart disease; controlled study; executive function; Fallot tetralogy; female; great vessels transposition; heart single ventricle; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; latent class analysis; major clinical study; male; prematurity; priority journal; pulmonary valve atresia; quality of life; questionnaire; social psychology; structural equation modeling

Home- and hospital-based exercise training programme after Fontan surgery - Sutherland, N.; Jones, B.; Westcamp Aguero, S.; Melchiori, T.; Du Plessis, K.; Konstantinov, I.E.; Cheung, M.M.H.; D'Udekem, Y. (Cardiology in the Young, 2018)
Background Exercise training has been shown to increase exercise capacity in survivors of Fontan surgery. The geographic distribution of the Fontan population has been a barrier to hospital-based exercise training programmes. The objective of this study was to establish whether a home exercise training programme could achieve similar improvements to a hospital programme.Methods Adolescents with a Fontan circulation aged 12-19 years were prospectively recruited in a hospital or home exercise training programme. Patients underwent cardiopulmonary exercise testing and completed the Paediatric Quality of Life Inventory at initial assessment and after completion of an 8-week programme. Both groups performed two 1-hour training sessions per week. Patients in the home training programme had their first session in the hospital, and then progressed independently with one phone consult per week and one home visit by a physiotherapist.Results In total, 17 patients, with a mean age of 15±3 years, completed the training programme (six hospital). Characteristics and baseline performance of patients were similar in both groups. Oxygen consumption at anaerobic threshold increased from 19.3±3.8 to 21.6±6.0 ml/kg/minute (p=0.02) and peak oxygen pulse increased from 8.8±2.5 to 9.5±2.7 ml/beat (p=0.049). Total quality of life scale improved from 68 to 74% (p=0.01) and psychosocial health improved from 67 to 74% (p=0.02). No patient experienced training-related complications.Conclusions Exercise training is beneficial and most likely safe after Fontan, resulting in improved exercise capacity and self-reported quality of life. Home exercise training programmes are probably as effective as hospital programmes. Home exercise training programmes should be integrated in the follow-up care of patients undergoing Fontan surgery.
Keywords: adolescent; adult; anaerobic exercise; article; cardiopulmonary exercise test; child; clinical article; controlled study; exercise; female; Fontan procedure; home care; home visit; hospital care; human; male; oxygen consumption; Pediatric Quality of Life Inventory; physiotherapist; postoperative period; prospective study; pulse rate; quality of life; social psychology; teleconsultation

Maternal Distress and Infant Social Withdrawal (ADBB) Following Infant Cardiac Surgery for Congenital Heart Disease - Re, J.M.; Dean, S.; Mullaert, J.; Guedeney, A.; Menahem, S. (World Journal for Pediatric and Congenital Heart Surgery, 2018)
Background: Mothers and infants are exposed to multiple stresses when cardiac surgery is required for the infant. This study reviewed infant responsiveness using a standardized objective observational measure of social withdrawal and explored its association with measures of maternal distress. Methods: Mother–infant pairs involving infants surviving early cardiac surgery were assessed when the infant was aged two months. Infant social withdrawal was measured using the Alarm Distress Baby Scale. Maternal distress was assessed using self-report measures for maternal depression (Edinburgh Postnatal Depression Scale), anxiety (Spielberger State-Trait Anxiety Scale), and parenting stress (Parenting Stress Index–Short Form). Potential associations between infant social withdrawal and maternal distress were evaluated. Results: High levels of maternal distress and infant social withdrawal were identified relative to community norms with a positive association. Such an association was not found between infant social withdrawal and the cardiac abnormality and surgery performed. Conclusion: The vulnerability of infants requiring cardiac surgery may be better understood when factors beyond their medical condition are considered. The findings suggested an association between maternal distress and infant social withdrawal, which may be consistent with mothers’ distress placing infants subjected to cardiac surgery at substantially increased risk of social withdrawal. However, it is unclear to what extent infant withdrawal may trigger maternal distress and what the interactive effects are. Further research is warranted. Trialing a mother–infant support program may be helpful in alleviating distress and improving the well-being and outcomes for these families.
Keywords: adult; anxiety; aortic coarctation; article; Bayley Scales of Infant Development; clinical article; congenital heart disease; depression; Edinburgh Postnatal Depression Scale; facial expression; female; heart atrium septum defect; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; infant; Likert scale; male; maternal stress; mother child relation; New York Heart Association class; parental stress; Parenting Stress Index Short Form; postnatal depression; predictive value; priority journal; psychosocial withdrawal; social adaptation; State Trait Anxiety Inventory; stress assessment; treatment outcome; vocalization

Home- and hospital-based exercise training programme after Fontan surgery - Sutherland, N.; Jones, B.; Westcamp Aguero, S.; Melchiori, T.; du Plessis, K.; Konstantinov, I.E.; Cheung, M.M.H.; d'Udekem, Y. (Cardiology in the young, 2018)
BACKGROUND: Exercise training has been shown to increase exercise capacity in survivors of Fontan surgery. The geographic distribution of the Fontan population has been a barrier to hospital-based exercise training programmes. The objective of this study was to establish whether a home exercise training programme could achieve similar improvements to a hospital programme. METHODS: Adolescents with a Fontan circulation aged 12-19 years were prospectively recruited in a hospital or home exercise training programme. Patients underwent cardiopulmonary exercise testing and completed the Paediatric Quality of Life Inventory at initial assessment and after completion of an 8-week programme. Both groups performed two 1-hour training sessions per week. Patients in the home training programme had their first session in the hospital, and then progressed independently with one phone consult per week and one home visit by a physiotherapist. RESULTS: In total, 17 patients, with a mean age of 15±3 years, completed the training programme (six hospital). Characteristics and baseline performance of patients were similar in both groups. Oxygen consumption at anaerobic threshold increased from 19.3±3.8 to 21.6±6.0 ml/kg/minute (p=0.02) and peak oxygen pulse increased from 8.8±2.5 to 9.5±2.7 ml/beat (p=0.049). Total quality of life scale improved from 68 to 74% (p=0.01) and psychosocial health improved from 67 to 74% (p=0.02). No patient experienced training-related complications. CONCLUSIONS: Exercise training is beneficial and most likely safe after Fontan, resulting in improved exercise capacity and self-reported quality of life. Home exercise training programmes are probably as effective as hospital programmes. Home exercise training programmes should be integrated in the follow-up care of patients undergoing Fontan surgery.
Keywords: adolescent; child; clinical trial; congenital heart malformation; exercise tolerance; female; Fontan procedure; home care; hospital patient; human; kinesiotherapy; male; multicenter study; pathophysiology; physiology; postoperative care; procedures; quality of life; questionnaire; treatment outcome; young adult

Genetic and Extracardiac Anomalies Are Associated With Inferior Single Ventricle Palliation Outcomes - Alsoufi, B.; McCracken, C.; Oster, M.; Shashidharan, S.; Kanter, K. (Annals of Thoracic Surgery, 2018)
Background: We examined the effect of genetic syndromes and extracardiac (GS/EC) anomalies on single-ventricle (SV) palliation with focus on hospital and interstage death and progression toward subsequent palliation stages. Methods: First-stage palliation was performed in 530 neonates with SV: Norwood in 284 (53%), shunt in 173 (33%), and band in 73 (14%). Outcomes were compared between those with GS/EC anomalies (121 [23%]) and without GS/EC anomalies (409 [77%]). Regression analyses were adjusted for other risk factors (age, sex, prematurity, weight, SV anomaly, and first-stage palliation operation). Results: GS/EC anomalies varied among SV defects (range, 3% for double-inlet left ventricle to 100% for atrial isomerism). Patients with GS/EC anomalies required significantly longer durations of mechanical ventilation and intensive care unit and hospital stay. Although patients had comparable rates of extracorporeal membrane oxygenation (13% vs 11%, p = 0.552) and unplanned reoperation (16% vs 11%, p = 0.189), hospital mortality was higher in patients with GS/EC anomalies (24% vs 12%, p = 0.0008). After discharge, patients with GS/EC anomalies had higher interstage death, with lower progression to Glenn (60% vs 77%, p = 0.002) and lower 10-year survival (56% vs 76%, p < 0.001). After adjustment for other risk factors, GS/EC anomalies significantly affected survival in almost all subgroups of patients. Conclusions: The presence of GS/EC anomalies varies among SV anomalies and is associated with additional risk factors such as prematurity and low weight. After adjusting for other risk factors, GS/EC anomalies are associated with prolonged recovery after first-stage palliation and increased hospital and interstage death, with subsequently fewer patients progressing toward Glenn shunt. The increased death risk in those patients is highest in the first 6 months and persists for 2 to 3 years after first-stage palliation, suggesting the need for more vigilant monitoring and outpatient care in these high-risk patients.
Keywords: anus atresia; article; artificial ventilation; Blalock Taussig shunt; child; chromosome aberration; chromosome analysis; chromosome deletion 22q11; comparative study; congenital heart disease; congenital ichthyosiform erythroderma; coronary care unit; Dandy Walker syndrome; disease association; disease course; Down syndrome; extracardiac anomaly; extracorporeal oxygenation; female; follow up; genetic anomaly; genetic disorder; heart single ventricle; heart transplantation; heterotaxy syndrome; high risk patient; Hirschsprung disease; hospital mortality; hospitalization; human; hypoplastic left heart syndrome; in situ hybridization; intensive care unit; intestine atresia; karyotype; Klinefelter syndrome; limb defect; major clinical study; male; medical record; monosomy; newborn; newborn screening; Norwood procedure; omphalocele; outcome assessment; outpatient care; palliative therapy; patient monitoring; priority journal; reoperation; risk assessment; risk factor; survival; syndrome CHARGE; tracheoesophageal fistula; Turner syndrome

Efficacy of Sports Club Activities on Exercise Tolerance Among Japanese Middle and High School Children and Adolescents After Fontan Procedure - Kodama, Y.; Koga, K.; Kuraoka, A.; Ishikawa, Y.; Nakamura, M.; Sagawa, K.; Ishikawa, S. (Pediatric Cardiology, 2018)
The exercise tolerance of Fontan patients is poorer than that of healthy people. Some previous studies reported that exercise tolerance can be improved in this population by cardiac rehabilitation. This study aimed to determine the factors associated with peak oxygen uptake (VO2) and to subsequently clarify the correlation between participation in sports club activities and variables related to exercise tolerance. Cardiopulmonary exercise tests were performed by 115 Fontan patients aged between 6 and 20 years. The patients completed questionnaires on their daily physical activities including participation in extracurricular sports clubs in middle (junior high school) and high school. Peak VO2 had a significant negative correlation with age and a positive correlation with hemoglobin, stroke volume, and resting tidal volume in the entire study group. Additionally, the sports club participants who were middle and high school students had significantly higher peak VO2 and resting tidal volume. Exercise habits including participation in sports club activities may promote exercise tolerance by improving respiratory function in Fontan adolescents.
Keywords: hemoglobin; adolescent; adult; age; article; cardiopulmonary exercise test; child; controlled study; correlation analysis; exercise tolerance; female; Fontan procedure; heart stroke volume; hemoglobin blood level; high school student; human; major clinical study; male; middle school student; oxygen consumption; patient participation; physical activity; preschool child; questionnaire; respiratory function; school child; sport; tidal volume; young adult

Cerebrovascular response to maternal hyperoxygenation in fetuses with hypoplastic left heart syndrome depends on gestational age and baseline cerebrovascular resistance - Szwast, A.; Putt, M.; Gaynor, J.W.; Licht, D.J.; Rychik, J. (Ultrasound in obstetrics & gynecology : the official journal of the International Society of Ultrasound in Obstetrics and Gynecology, 2018)
OBJECTIVES: Compared with normal fetuses, fetuses with hypoplastic left heart syndrome (HLHS) have smaller brain volumes and are at higher risk of brain injury, possibly due to diminished cerebral blood flow and oxygen content. By increasing cerebral oxygen delivery, maternal hyperoxygenation (MH) might improve brain development and reduce the risk of brain injury in these fetuses. This study investigated whether gestational age and baseline cerebrovascular resistance affect the response to MH in fetuses with HLHS. METHODS: The study population comprised 43 fetuses with HLHS or HLHS variant referred for fetal echocardiography between January 2004 and September 2008. Middle cerebral artery (MCA) pulsatility index (PI), a surrogate measure of cerebrovascular resistance, was assessed between 20 and 41 weeks' gestation at baseline in room air (RA) and after 10 min of MH. Z-scores of MCA-PI were generated. A mixed-effects model was used to determine whether change in MCA-PI depends upon gestational age and baseline MCA-PI. RESULTS: In RA and following MH, MCA-PI demonstrated a curvilinear relationship with gestational age in fetuses with HLHS, peaking at around 28 weeks and then falling more steeply near term. MCA-PI Z-score declined in a linear manner, such that it was 1.4 SD below that in normal fetuses at 38 weeks. Increase in MCA-PI Z-score after MH was first seen at ≥ 28 weeks. A baseline MCA-PI Z-score ≤ -0.96 was predictive of an increase in cerebrovascular resistance in response to MH. CONCLUSION: In fetuses with HLHS, MCA-PI first increases in response to MH at ≥ 28 weeks' gestation. A baseline MCA-PI Z-score ≤ -0.96 predicts an increase in cerebrovascular resistance in response to MH. These results may have implications for clinical trials utilizing MH as a neuroprotective agent. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: oxygen; adult; blood; brain circulation; diagnostic imaging; echocardiography; embryology; female; fetus echography; fetus monitoring; gestational age; human; hypoplastic left heart syndrome; mental disease; metabolism; middle cerebral artery; mother; newborn; oxygen therapy; pathophysiology; physiology; placenta; pregnancy; pulsatile flow; treatment outcome; vascularization

Grief and coping of parents whose child has a constant life-threatening disability, hypoplastic left heart syndrome with reference to the Dual-Process Model - Cantwell-Bartl, A. (Death studies, 2018)
This paper reports on a study that examined the grief and coping of 29 parents whose child has hypoplastic left heart syndrome using the Dual Process Model. The study employed a secondary thematic analysis of interviews at key times of treatment and recovery for the child. After the diagnosis, parents experienced intense loss (LO), but focused upon restoration-orientated tasks (RO) to support their child. Over time, most parents employed a healthy oscillation between LO coping and RO coping, with waves of grief and with some grieving suppressed. There are some specific grief and coping and gender patterns employed by parents.
Keywords: adult; child; child parent relation; classification; coping behavior; female; grief; handicapped child; human; hypoplastic left heart syndrome; male; nursing; psychological model; psychology

Tricuspid valve replacement in failing Fontan circulation with severe ventricular dysfunction: The road not taken? - Perrier, S.L.; Zhu, M.Z.L.; Weintraub, R.G.; Konstantinov, I.E. (Journal of Thoracic and Cardiovascular Surgery, 2018)
Keywords: annuloplasty ring; dual chamber pacemaker; polytetrafluoroethylene; polytetrafluoroethylene implant; acetylsalicylic acid; diuretic agent; lactic acid; lisinopril; oxygen; arterial gas; article; assisted circulation; atresia; autism; cardiopulmonary bypass; case report; child; clinical article; complete heart block; echocardiography; extracorporeal oxygenation; Fontan procedure; heart failure; heart transplantation; hospital discharge; human; hypoplastic left heart syndrome; male; mitral valve atresia; oxygen saturation; oxygen tension; pH; preschool child; priority journal; tricuspid annuloplasty; tricuspid valve replacement; Carpentier-Edwards Physio; GORE-TEX

A survey of health professionals’ views on acceptable gestational age and termination of pregnancy for fetal anomaly - Crowe, L.; Graham, R.H.; Robson, S.C.; Rankin, J. (European Journal of Medical Genetics, 2018)
Termination of pregnancy for fetal anomaly is legal in the UK with no upper limit, if two doctors, in good faith, agree “there is a substantial risk that if the child were born it would suffer from such physical or mental abnormalities as to be seriously handicapped”. This is Clause E of the Human Fertlisation and Embryology Act. The most commonly sighted Clause is C, which states “the pregnancy has not exceeded its twenty-fourth week and that the continuance of the pregnancy would involve risk, greater than if the pregnancy were terminated, of injury to the physical or mental health of the pregnant woman”. This study aimed to investigate health professionals’ views on gestational age and acceptable termination of pregnancy for fetal anomaly (TOPFA). We undertook a questionnaire survey of UK health professionals working in fetal medicine, obstetrics and gynaecology and neonatology. A study pack consisting of a self-completion questionnaire, an invitation letter, participant information sheet, and a stamped addressed return envelope, were sent to health professionals. We used four fetal anomalies as case study examples in the questionnaire: isolated cleft lip, hypoplastic left heart, spina bifida and trisomy 21. These anomalies were chosen as they differed in terms of the type of anomaly, the type of impairment, and the perceived severity. Forty-one study packs were returned. For anomalies deemed less serious, later gestational ages were an important consideration when deciding acceptable TOPFA. The prognosis of an anomaly was considered an important factor in deciding whether a TOPFA was acceptable alongside gestational age. Clause C of the current UK legislation, which allows a legal termination prior to 24 weeks gestational age if continuing with the pregnancy would impact the mental health of the mother, was deemed a reasonable option for termination when parents are requesting a TOPFA. For each case study example, health professionals responded that TOPFA at ‘25 weeks and over’ was acceptable (cleft lip n = 1; hypoplastic left heart n = 19; spina bifida n = 13 and Trisomy 21 n = 10). Professionals also distinguished between their personal and professional views. These findings offer new insight into how gestational age considerations influence professionals’ conceptualisation of acceptable TOPFA.
Keywords: article; cleft lip; disease severity; female; fetus malformation; gestational age; gynecology; health personnel attitude; health practitioner; health survey; human; hypoplastic left heart syndrome; law; male; medical information; mental health; neonatology; pregnancy termination; prognosis; questionnaire; spinal dysraphism; trisomy 21; United Kingdom

Can a home-based cardiac physical activity program improve and sustain quality of life and exercise capacity in children with Fontan circulation? - Jacobsen, R.; Danduran, M.; Mussatto, K.; Hill, G.D.; Ginde, S. (Progress in Pediatric Cardiology, 2018)
Objective: Fontan survivors report reduced health-related quality of life (HRQOL) and have decreased exercise tolerance compared to healthy peers. We recently demonstrated that a 12-week home-based physical activity program was safe, feasible, and improved parent proxy-reported HRQOL and objective measures of exercise capacity in patients with Fontan circulation. We sought to determine if these improvements in HRQOL and exercise capacity are sustained at 6-month follow-up. Design: Patients, 8–12 years old, with Fontan circulation that completed a 12-week moderate-to-vigorous intensity home-based physical activity program were invited to attend a 6-month follow-up session to complete objective assessments of HRQOL and exercise capacity. HRQOL was measured with validated questionnaires. The 20-meter Shuttle Run (PACER Test) was used to measure exercise capacity. Results: Of the 13 patients who completed the original 12-week physical activity program, 11 (85%) attended the 6-month follow-up. There were no adverse events during the follow-up period. Improvements in parent proxy-report for HRQOL at completion of the 12-week program were sustained at 6-month follow-up. Patients reported a significant decrease in HRQOL assessed by PedsQL at 6-month follow-up. However, there was a non-significant trend of improvement in patient PCQLI total and psychosocial impact scores at completion of the 12-week program, which was sustained at 6-month follow-up. The significant improvements in objective measures of exercise capacity seen from baseline to completion of the 12-week program were sustained at 6-month follow-up. Conclusion: Improvements in parent-proxy report HRQOL and objective measures of exercise capacity after completion of a home-based 12-week physical activity program were sustained at 6-month follow-up. Despite improvements in exercise capacity, patients did not report improved HRQOL. A larger, controlled study of this home-based physical activity program is needed to assess the impact of physical activity and improved exercise capacity on HRQOL in children with Fontan circulation.
Keywords: article; child; clinical article; exercise; exercise intensity; exercise test; exercise tolerance; female; follow up; Fontan procedure; functional status; home physiotherapy; human; male; physical activity; priority journal; quality of life; quality of life assessment; questionnaire; school child; social psychology; survivor; treatment duration; Twenty Meter Shuttle Run

Use of low-dose dexmedetomidine in combination with opioids and midazolam in pediatric cardiac surgical patients: Randomized controlled trial - Garisto, C.; Ricci, Z.; Tofani, L.; Benegni, S.; Pezzella, C.; Cogo, P. (Minerva Anestesiologica, 2018)
BACKGROUND: Dexmedetomidine is a selective agonist of α2 receptors that induces hypnotic, sedative and mild analgesic effect. The aim of our study was to test the effects of dexmedetomidine in combination with opioids and benzodiazepines compared to benzodiazepine-opioids alone. METHODS: Arandomized controlled trial was conducted. Patients (children >30 days and <24 months undergoing correction of complex congenital heart diseases [CHD]) were randomized to receive 0.5 mcg/kg/h dexmedetomidine in addition to half dose of opioids and benzodiazepines (D-CASES) or standard dose opioids and benzodiazepines (CONTROLs). Primary outcome: to compare the duration of mechanical ventilation (MV) in D-CASEs and CONTROLs. Secondary outcomes: 1) the degree of sedation; 2) the onset of withdrawal symptoms; 3) the occurrence bradycardia and hypotension. RESULTS: Overall, 48 patients, 26 in CONTROLs group and 22 in D-CASEs group were ultimately included in the analysis after enrollment. The median duration of MV was 33.5 (16.7-75) hours in CONTROLs and 41.5 (23.7-71.2) hours in D-CASEs (P=0.51). Dexmedetomidine did not affect COMFORTand FLACCscales but it reduced the SOSscale in 15 D-CASEs vs. 11 CONTROLs (P=0.001). The incidence of bradycardia and hypotension and vasoactive support did not show significant differences in the two groups. CONCLUSIONS: Low dose of dexmedetomidine in combination with morphine and midazolam was safe in a high-risk cohort of CHD children after cardiac surgery and reduced the onset of withdrawal symptoms. However, it did not decrease MV time and the total amount of other sedative and analgesic drugs required in the post-operative period.
Keywords: NCT02375243; dexmedetomidine; midazolam; opiate; aortic arch interruption; aortic regurgitation; article; artificial ventilation; bradycardia; cardiopulmonary bypass; clinical article; comparative study; congenital heart disease; controlled study; Fallot tetralogy; female; heart atrium septum defect; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; hypotension; infant; male; mitral valve regurgitation; newborn; pulmonary artery aneurysm; pulmonary valve atresia; pulmonary valve stenosis; pulmonary vein stenosis; randomized controlled trial; sedation; systolic blood pressure; withdrawal syndrome

Cerebral Autoregulation in Neonates With and Without Congenital Heart Disease - Tran, N.N.; Kumar, S.R.; Hodge, F.S.; Macey, P.M. (American journal of critical care : an official publication, American Association of Critical-Care Nurses, 2018)
BACKGROUND: Congenital heart disease (CHD) is a leading birth defect in the United States, affecting about 40 000 neonates each year. Despite efforts to prevent developmental delays, many children with CHD have neurological deficits that last into adulthood, influencing employability, self-care, and quality of life. OBJECTIVE: To determine if neonates with CHD have impaired cerebral autoregulation and poorer neurodevelopmental outcomes compared with healthy controls. METHODS: A total of 44 full-term neonates, 28 with CHD and 16 without, were enrolled in the study. Inclusion criteria included confirmed diagnosis of CHD, stable hemodynamic status, and being no more than 12 days old. Exclusion criteria included intraventricular hemorrhage and intubation. Cerebral autoregulation was determined by measuring regional cerebral oxygenation during a postural change. The Einstein Neonatal Neurobehavioral Assessment Scale was used to measure overall neurodevelopmental outcomes (motor, visual, and auditory functions). RESULTS: Of the 28 neonates with CHD, 8 had single-ventricle physiology. A χ2 analysis indicated no significant difference in impaired cerebral autoregulation between neonates with CHD and controls (P = .38). Neonates with CHD had lower regional cerebral oxygenation than did neonates without CHD (P < .001). Regression analyses with adjustments for cerebral autoregulation indicated that neonates with CHD had poorer total neurodevelopmental outcomes scores (β = 9.3; P = .02) and motor scores (β = 7.6; P = .04). CONCLUSION: Preoperative neonates with CHD have poorer developmental outcomes and more hypoxemia than do controls.
Keywords: oxygen; brain; case control study; complication; congenital heart malformation; cross-sectional study; developmental disorder; female; homeostasis; human; hypoxia; male; metabolism; near infrared spectroscopy; neurologic examination; newborn; pathophysiology; physiology; prospective study

Pulmonary vascular disease in a failed fontan patient with down’s syndrome - Aoki, M.; Hirono, K.; Higuma, T.; Suzuki, Y.; Nakayama, K.; Yamashita, A.; Fukahara, K.; Ichida, F.; Emoto, N.; Yoshimura, N. (General Thoracic and Cardiovascular Surgery, 2018)
It is well known that Down’s syndrome is a strong risk factor for mortality after Fontan operations. We performed two lung biopsies in a Down’s syndrome patient who underwent staged Fontan operations. The pathological findings revealed severe pulmonary arterial hypertrophy and a quantitative real-time polymerase chain reaction revealed the overexpression of endothelin and a decline in the eNOS level at the Fontan operation. Although the preoperative hemodynamic studies revealed that all of the criteria for Fontan had been fulfilled, the patient died of acute cardiac insufficiency, 35 days after the Fontan operation.
Keywords: LightCycler96 system; polymerase chain reaction system; endothelial nitric oxide synthase; endothelin; polytetrafluoroethylene; RNA; acute heart failure; aortic clamping; article; atrioventricular septal defect; cardiopulmonary bypass; case report; cesarean section; child; clinical article; congenital heart malformation; disease association; Down syndrome; echocardiography; Fallot tetralogy; fetus echography; Fontan procedure; gene overexpression; Glenn shunt; heart catheterization; heart ventricle septum defect; human; human tissue; hypothermia; lung artery pressure; lung biopsy; lung disease; lung vascular resistance; male; operation duration; preoperative evaluation; preschool child; pulmonary coarctation; pulmonary vascular disease; real time polymerase chain reaction; reverse transcription polymerase chain reaction; treatment failure; LightCycler96 system

Pulmonary Screening in Subjects after the Fontan Procedure - Liptzin, D.R.; Di Maria, M.V.; Younoszai, A.; Narkewicz, M.R.; Kelly, S.L.; Wolfe, K.R.; Veress, L.A. (Journal of Pediatrics, 2018)
Objectives: To review the pulmonary findings of the first 51 patients who presented to our interdisciplinary single-ventricle clinic after undergoing the Fontan procedure. Study design: We performed an Institutional Review Board–approved retrospective review of 51 patients evaluated following the Fontan procedure. Evaluation included history, physical examination, pulmonary function testing, and 6-minute walk. Descriptive statistics were used to describe the population and testing data. Results: Sixty-one percent of the patients had a pulmonary concern raised during the visit. Three patients had plastic bronchitis. Abnormal lung function testing was present in 46% of patients. Two-thirds (66%) of the patients had significant desaturation during the 6-minute walk test. Patients who underwent a fenestrated Fontan procedure and those who underwent unfenestrated Fontan were compared in terms of saturation and 6-minute walk test results. Sleep concerns were present in 45% of the patients. Conclusions: Pulmonary morbidities are common in patients after Fontan surgery and include plastic bronchitis, abnormal lung function, desaturations with walking, and sleep concerns. Abnormal lung function and obstructive sleep apnea may stress the Fontan circuit and may have implications for cognitive and emotional functioning. A pulmonologist involved in the care of patients after Fontan surgery can assist in screening for comorbidities and recommend interventions.
Keywords: adolescent; adult; article; bronchitis; child; female; fenestration; Fontan procedure; human; institutional review; lung function test; major clinical study; male; medical record review; outpatient department; physical examination; priority journal; retrospective study; screening test; six minute walk test

Characterization of the Placenta in the Newborn with Congenital Heart Disease: Distinctions Based on Type of Cardiac Malformation - Rychik, J.; Goff, D.; McKay, E.; Mott, A.; Tian, Z.; Licht, D.J.; Gaynor, J.W. (Pediatric Cardiology, 2018)
The placenta is a complex organ that influences prenatal growth and development, and through fetal programming impacts postnatal health and well-being lifelong. Little information exists on placental pathology in the presence of congenital heart disease (CHD). Our objective is to characterize the placenta in CHD and investigate for distinctions based on type of malformation present. Placental pathology from singleton neonates prenatally diagnosed and delivered at > 37 weeks gestation was analyzed. Placental findings of absolute weight, placental weight-to-newborn birth weight ratio, chorangiosis, villus maturity, thrombosis, and infarction were recorded and analyzed based on four physiological categories of CHD: (1) single ventricle-aortic obstruction, (2) single ventricle-pulmonic obstruction, (3) two-ventricle anomalies, and (4) transposition of the great arteries (TGA). Associations between fetal Doppler assessments of middle cerebral/umbilical arterial flow and placental findings were investigated. A total of 120 cases of complex CHD were analyzed. Overall placental-to-birth weight ratios were < 10th percentile for 77% and < 3rd percentile for 49% with abnormalities of chorangiosis (18%), hypomature villi (15%), thrombosis (41%), and infarction (17%) common. There was no association between fetal Doppler flow measures and placental abnormalities. Newborns with TGA had the greatest degree of placental abnormality. Placentas of newborns with CHD are smaller than expected and manifest a number of vascular abnormalities, with TGA most prominent. Fetal Doppler does not correlate with these abnormalities. Studies investigating the relationship between placental abnormalities and postnatal outcomes may offer insight into the fetal origins of outcome variability in CHD.
Keywords: aortic occlusion; artery blood flow; article; birth weight; cardiovascular malformation; chorion villus; cohort analysis; congenital heart disease; Doppler echocardiography; fetus; gestational age; great vessels transposition; human; infarction; major clinical study; middle cerebral artery; newborn; obstetric delivery; placenta; placenta weight; pulmonary valve stenosis; thrombosis; umbilical artery

Can the inevitable be prevented? – An analysis of loss to follow-up among grown-ups with congenital heart disease in Malta - Caruana, M.; Aquilina, O.; Grech, V. (Malta Medical Journal, 2018)
Aims: To investigate the prevalence of loss to follow-up, factors predisposing to loss to follow-up and the outcome of recall into specialist care among grown-ups with congenital heart disease (GUCH) of moderate or severe complexity prior to the introduction of formal transition in Malta. Methods: Medical documentation for all live patients with tetralogy of Fallot, aortic coarctation/interrupted aortic arch, partial and complete atrioventricular septal defect, Fontan-type circulation and transposition of the great arteries in our institutional database aged ≥16 years was analysed to determine follow-up status. Patients lost to follow-up were recalled through a postal appointment. Ordinal logistic regression was used to analyse the effect of gender, CHD complexity, consistency of paediatric cardiology follow-up during childhood, number of cardiac surgical/interventional procedures and use of longterm cardiac medications on loss to follow-up. Results: Forty-one of 187 patients (21.9%) (27 males; 34 with moderate disease) had been lost to follow-up. Limited paediatric cardiology input (OR, 5.08; 95% CI, 1.77-14.63) (p=0.003), ≤1 surgical/interventional procedures (OR, 3.34; 95% CI, 1.09-10.26) (p=0.035) and no long-term cardiac medications (OR 7.34; 95% CI, 1.74-31.02) (p=0.007) were associated with higher risk of loss to follow-up. A positive response to recall was obtained from 33/41 (80.5%) patients. Significant cardiac morbidity was found in 5/33 (15.2%) patients upon reassessment. Conclusions: Loss to specialist follow-up occurs even in health systems with little perceived barriers to medical care. Consistent specialist input during all stages and patient and family education through formal transition can help ensure a smoother transfer to GUCH care.
Keywords: adult; aortic arch anomaly; aortic coarctation; article; congenital heart disease; Fallot tetralogy; female; follow up; great vessels transposition; human; major clinical study; male; mitral valve regurgitation; patient dropout; prevalence; prognosis; pulmonary valve insufficiency; pulmonary valve replacement; pulmonary valve stenosis; pulmonary valvuloplasty; transition to adult care; transluminal valvuloplasty

Cancer management in kabuki syndrome: The first case of wilms tumor and a literature review - Teranishi, H.; Koga, Y.; Nakashima, K.; Morihana, E.; Ishii, K.; Sakai, Y.; Taguchi, T.; Oda, Y.; Miyake, N.; Matsumoto, N.; Ohga, S. (Journal of Pediatric Hematology/Oncology, 2018)
A 3-year-old Japanese girl treated for hypoplastic left heart syndrome and Dandy-Walker syndrome was diagnosed with Kabuki syndrome (KS) with a mutation of KMT2D; c.13285C>T:p.Q4429∗. Concurrently, macrohematuria portended the diagnosis of Wilms tumor. Postoperative chemotherapy has achieved complete remission despite a prolonged and reduced regimen due to liver dysfunction and convulsions. Cancer predisposition has been suggested for KS due to oncogenic mutations in KMT2D or KDM6A. The first case of nephroblastoma exemplified the treatability of malignancies in KS patients, as shown in the 9 cases reviewed. Active screening and intervention are recommended for the cure of malignancy in KS children.
Keywords: dactinomycin; DNA; vincristine; article; brain ventricle peritoneum shunt; cancer regression; cancer surgery; case report; child; clinical article; computer assisted tomography; convulsion; Dandy Walker syndrome; drug dose reduction; female; gene; gene mutation; Glenn shunt; hematuria; histopathology; human; human cell; human tissue; hypoplastic left heart syndrome; infant; Japanese (people); Kabuki makeup syndrome; KMT2D gene; liver dysfunction; nephroblastoma; Norwood procedure; nuclear magnetic resonance imaging; peripheral blood mononuclear cell; preschool child; priority journal; Sanger sequencing; seizure; whole exome sequencing

Perception scores of siblings and parents of children with hypoplastic left heart syndrome - Caris, E.C.; Dempster, N.; Wernovsky, G.; Miao, Y.; Moore-Clingenpeel, M.; Neely, T.; Fonseca, R.; Miller-Tate, H.; Allen, R.; Fichtner, S.; Stewart, J.; Cua, C.L. (Congenital Heart Disease, 2018)
Objectives: Siblings of children with chronic medical conditions endorse a lower quality of life compared to age-matched peers. Caregiver and sibling-self report of adjustment are often discordant. Congenital heart disease significantly affects family life. To date, there have been no studies addressing the functioning of siblings of children with hypoplastic left heart syndrome, one of the most severe forms of congenital heart disease. The goal of this study was to assess the impact of hypoplastic left heart syndrome on sibling's quality of life as well as the caregiver's perception of this effect. Study Design: Cross-sectional study using a web-based survey distributed via various listservs targeted towards families of children with hypoplastic left heart syndrome. Employed the Sibling Perception Questionnaire, designed to assess sibling and caregiver perceptions of adjustment to chronic illness. A Negative Adjustment Composite Score was calculated for each respondent, with higher values representing more negative adjustment. Results: Thirty-five caregivers responded. Majority of caregivers were female (74%), white (86%) and college educated (54%). Thirty-two siblings participated, ranging in age from 7 to 30 years of age (12.5 ± 6.3). Most children with hypoplastic left heart syndrome (73%) had undergone the third stage of palliation. Forty-two caregiver-sibling pairs were examined. Caregiver Negative Adjustment Composite Scores were significantly higher than sibling scores, with caregivers reporting more adjustment problems (2.4 ± 0.4) than siblings (2.3 ± 0.3, P <.05). Sibling age was correlated with worse caregiver and sibling scores (r 0.35, P <.05). Conclusions: Caregivers of children with hypoplastic left heart syndrome perceive their siblings as struggling more than the children self-report. Siblings tend to report worse adjustment as they get older. These data suggest that programs should include support for the entire family through all ages to optimize quality of life.
Keywords: adolescent; adult; article; caregiver; child; controlled study; cross-sectional study; family attitude; female; human; hypoplastic left heart syndrome; male; Negative Adjustment Composite Score; parent; pediatrics; perception; perception test; priority journal; prospective study; quality of life; self report; sibling; Sibling Perception Questionnaire

Transition experiences between hospital- and home-care for parents of children with hypoplastic left heart syndrome - March, S.; Keim-Malpass, J. (Journal for specialists in pediatric nursing : JSPN, 2018)
PURPOSE: Children with hypoplastic left heart syndrome (HLHS) experience numerous vulnerabilities during transitions from hospital to home during their first year of life. This paper examines the parents' responses to the situations they experience during the initial interstage transition as described through illness blogs. DESIGN AND METHODS: A qualitative descriptive design through inductive theme development using thematic analysis was performed for this study. Text data were used from publically available blogs written by parents of HLHS children on their feelings and experiences during transitions between hospital- and home-care during the interstage period. RESULTS: Six blogs were analyzed. Overall, the lack of difference in normalcy for these parents and their families was apparent. Major themes included: thoughts and feelings when discharged from the hospital, difficulties with hospital readmissions, protecting their child from infection, and developing a support system. CONCLUSIONS: Parents looked forward to going home and learned all they could about properly caring for their child before going home. They were disappointed and frustrated when returning to the hospital for either emergency or scheduled admissions and were not prepared to see their child in the intensive care unit environment again. Many parents isolated themselves and avoided the hospital as much as possible to avoid their child developing an infection. All parents had support systems through family and/or friends and found an unexpected sense of support through their blog families.
Keywords: adult; blogging; child parent relation; coping behavior; female; home care; hospital discharge; human; hypoplastic left heart syndrome; infant; male; nursing; organization and management; preschool child; prognosis; psychology; qualitative research; risk assessment; transitional care; verbal communication

Impact of Ventricular Morphology on Fiber Stress and Strain in Fontan Patients - Ghelani, S.J.; Colan, S.D.; Azcue, N.; Keenan, E.M.; Harrild, D.M.; Powell, A.J.; Geva, T.; Rathod, R.H. (Circulation. Cardiovascular imaging, 2018)
BACKGROUND: Right ventricular (RV) morphology has been associated with adverse clinical outcomes in Fontan patients. The impact of RV versus left ventricular morphology on ventricular stress and strain in single ventricles is not well known. METHODS AND RESULTS: Cardiac magnetic resonance examinations in 193 patients with the Fontan circulation were retrospectively analyzed. Ventricular mass, volume, global circumferential and longitudinal strain, and global average end-systolic fiber stress were calculated using previously published methods. Compared with left ventricular morphology, RV morphology (48%) was associated with higher ventricular end-diastolic volume (110 mL/BSA1.3 versus 84 mL/BSA1.3, P<0.001), lower mass-to-volume ratio (0.46 versus 0.57, P<0.001), higher global average end-systolic fiber stress (23 kPa versus 20 kPa, P=0.002), worse global circumferential strain (-21% versus -24%, P<0.001), and higher prevalence of greater than or equal to moderate atrioventricular valve regurgitation (25% versus 6%, P<0.001). Ejection fraction and global longitudinal strain were similar between the groups. Death or listing for heart transplantation occurred in 24 (12%) with a median follow-up of 6.2 years. On univariate analysis, RV morphology, ventricular dilatation, and worse global circumferential strain were associated with this composite outcome. CONCLUSIONS: In comparison to Fontan patients with a dominant left ventricle, those with a dominant RV have higher fiber stress, a higher rate of ventricular dilatation, lower circumferential fiber shortening, and similar longitudinal shortening. RV morphology, ventricular dilation, and worse circumferential strain are associated with death or heart transplantation. The difference in myofiber architecture may contribute to suboptimal adaptation of the RV as a systemic ventricle.
Keywords: adolescent; child; comparative study; congenital heart malformation; diagnostic imaging; exercise test; female; Fontan procedure; heart catheterization; heart contraction; heart left ventricle function; heart right ventricle function; heart transplantation; heart ventricle; heart ventricle remodeling; human; male; mortality; nuclear magnetic resonance imaging; pathophysiology; retrospective study; risk factor; time factor; treatment outcome; young adult

Patterns of Transition Experience for Parents Going Home from Hospital with their Infant after First Stage Surgery for Complex Congenital Heart Disease - Gaskin, K.L. (Journal of pediatric nursing, 2018)
PURPOSE: The purpose of this study was to explore parents' experiences of one specific timepoint in their infant's journey: the transition from hospital to home, following the first stage of their infant's cardiac surgery for complex congenital heart disease. DESIGN AND METHODS: A prospective longitudinal mixed methods study, underpinned with Middle Range Transition Theory (Meleis, Sawyer, Im, Hilfinger Messias, & Schumacher, 2000). Face to face and telephone interviews were conducted and self-report forms completed by parents at four-time points: before discharge (T0), 2weeks after discharge (T1), 8weeks after discharge (T2) and after stage two surgery (T3). Interviews were transcribed verbatim before inductive thematic analysis. RESULTS: Parents were recruited over a 15-month period from 2013 to 2015. Twelve mothers and 4 fathers took part. The infants had functionally univentricular heart (left n=10, right n=1) and a systemic shunt dependent lesion, tetralogy of Fallot (n=1). Dynamic constructivist and constructionist social processes occurred for all parents, involving physical, physiological, psychological and cognitive elements within four 'patterns of experience', two of which 'safety and security' and 'love and support' are presented in this paper. IMPLICATIONS: Parental support is essential; parents need to be engaged in discharge planning process and given the opportunity to express their needs to ensure that discharge care is truly patient and family centered. CONCLUSIONS: Transition from hospital to home was complex and multi-faceted, with unanticipated physical and emotional transitions superimposed upon those that were expected.
Keywords: article; clinical article; controlled study; Fallot tetralogy; father; female; genetic transcription; heart single ventricle; heart surgery; hospital discharge; human; infant; male; mother; prospective study; security; self report; surgery; telephone interview; thematic analysis; theoretical study

“How long will I continue to be normal?” Adults with a Fontan circulation's greatest concerns - du Plessis, K.; Peters, R.; King, I.; Robertson, K.; Mackley, J.; Maree, R.; Stanley, T.; Pickford, L.; Rose, B.; Orchard, M.; Stewart, H.; d'Udekem, Y. (International Journal of Cardiology, 2018)
Background: Little is known about adults living with a Fontan circulation's concerns outside the scope of their clinical outcomes. We examined adults with a Fontan circulations' greatest concerns, as well as their concerns around anti-coagulation, pregnancy and finances. Methods: Adults with a Fontan circulation in the Australian and New Zealand Fontan Registry were invited to complete an anonymous online survey, of which 57 participated. A qualitative method approach using thematic analyses was used. Results: The greatest concerns for adults living with a Fontan circulation were fear of death/uncertainty around life expectancy which for many individuals colored their concerns around physical health, pregnancy and having children, quality of life and finances. Improving information about outcomes to patients with a Fontan circulation might alleviate uncertainties about their future. Conclusions: Fear of death is the primary concern of adults with a Fontan circulation. It may require improved communication and targeted psychological interventions. Physical exercise incorporated as part of their lifestyle should be encouraged to alleviate physical concerns and also improve psychological well-being.
Keywords: adult; article; confusion (uncertainty); congenital heart disease; death; ethnicity; exercise; fear; female; financial management; Fontan procedure; health status; human; life expectancy; major clinical study; male; physical capacity; pregnancy; priority journal; quality of life; self report

A Novel Mechanism for Improved Exercise Performance in Pediatric Fontan Patients After Cardiac Rehabilitation - Wittekind, S.; Mays, W.; Gerdes, Y.; Knecht, S.; Hambrook, J.; Border, W.; Jefferies, J.L. (Pediatric Cardiology, 2018)
Patients with a Fontan circulation have impaired exercise capacity. Cardiac rehabilitation (CR) has shown promise in enhancing peak exercise parameters in this population, but an improvement in submaximal exercise has not been consistently demonstrated. We assessed the hypothesis that participation in CR will be associated with more efficient oxygen extraction and ventilation during submaximal exercise. In this prospective study, pediatric Fontans completed two 60 min CR sessions per week for 12 weeks. Cardiopulmonary exercise testing and stress echocardiography were performed at baseline and last CR session, and then compared with a paired sample t test. Ten pediatric Fontans completed the study. Five had tricuspid atresia and five had hypoplastic left heart syndrome. No serious adverse events occurred during CR sessions. Peak indexed oxygen consumption increased by a mean of 3.7 mL/kg/min (95% CI 1.5–5.9; p = 0.004), and peak oxygen pulse increased by a mean of 0.9 mL/beat (95% CI 0.4–1.4; p = 0.004). The peak respiratory exchange ratio did not change significantly. The significant difference in oxygen pulse became evident during submaximal exercise without a corresponding difference in echocardiographic stroke volume. Indexed oxygen consumption at ventilatory anaerobic threshold increased by a mean of 3.0 mL/kg/min (95% CI − 0.07 to 6.0; p = 0.055). The slope for the volume of expired ventilation to volume of carbon dioxide production improved by a mean of 4.5 (95% CI − 8.4 to − 0.6; p = 0.03). We observed significant improvements in both submaximal and peak exercise performance in pediatric Fontans undergoing CR with no serious adverse events. These changes appeared to be mediated, at least in part, by more efficient oxygen extraction and ventilation.
Keywords: carbon dioxide; adolescent; adult; article; cardiopulmonary exercise test; child; clinical article; controlled study; exercise; female; Fontan procedure; heart rehabilitation; heart stroke volume; human; hypoplastic left heart syndrome; lung gas exchange; lung ventilation; male; oxygen consumption; prospective study; stress echocardiography; tricuspid valve atresia

Brain abnormalities in cognition, anxiety, and depression regulatory regions in adolescents with single ventricle heart disease - Pike, N.A.; Roy, B.; Gupta, R.; Singh, S.; Woo, M.A.; Halnon, N.J.; Lewis, A.B.; Kumar, R. (Journal of Neuroscience Research, 2018)
Background: Single ventricle heart disease (SVHD) adolescents show cognitive impairments and anxiety and depressive symptoms, indicating the possibility of brain injury in regions that control these functions. However, brain tissue integrity in cognition, anxiety, and depression regulatory sites in SVHD remains unclear. We examined brain tissue changes in SVHD compared to controls using T2-relaxometry procedures, which measure free water content and show tissue injury. Methods: Proton-density and T2-weighted images, using a 3.0-Tesla MRI, as well as anxiety (Beck anxiety inventory [BAI]), depressive symptoms (patient health questionnaire-9 [PHQ-9]), and cognition (wide range assessment of memory and learning 2 [WRAML2] and Montreal cognitive assessment [MoCA]) data were collected from 20 SVHD (age: 15.8 ± 1.1 years, male/female: 11/9) and 36 controls (age: 16.0 ± 1.1 years, male/female: 19/17). Whole-brain T2-relaxation maps were calculated, normalized to a common space, smoothed, and compared between groups and sexes (analysis of covariance; covariates: age, sex; p < 0.001). Results: SVHD subjects showed significantly increased BAI and PHQ-9 and reduced MoCA and WRAML2 scores over controls. Several brain regions in SVHD showed increased T2-relaxation values (chronic injury), including the cingulate, and insula, hippocampus/para-hippocampal gyrus, thalamus, hypothalamus, amygdala, frontal white matter, corpus callosum, brainstem, and cerebellar areas. Decreased T2-relaxation values (acute injury) emerged in a few regions, including the prefrontal and cerebellar cortices in SVHD over controls. In addition, male SVHD showed more brain changes over female SVHD. Conclusions: Adolescents with SVHD showed significant brain injury with variable male–female differences in areas that control cognition, anxiety, and depression, which may contribute to functional deficits found in the condition.
Keywords: adolescent; amygdala; anxiety disorder; article; attention; Beck Anxiety Inventory; brain region; brain stem; brain tissue; cerebellum; clinical article; cognitive defect; comparative study; controlled study; corpus callosum; cross-sectional study; depression; female; heart single ventricle; hippocampus; human; hypothalamus; learning; male; memory; Montreal cognitive assessment; parahippocampal gyrus; Patient Health Questionnaire 9; prefrontal cortex; priority journal; sex difference; thalamus; vision; visual memory; white matter; working memory

Managing fertile women under lithium treatment: The challenge of a Teratology Information Service - Neri, C.; De Luca, C.; D'oria, L.; Licameli, A.; Nucci, M.; Pellegrino, M.; Caruso, A.; De Santis, M. (Minerva Ginecologica, 2018)
BACKGROUND: The objective of the present study is to review the literature regarding the management of fertile patients under lithium treatment for bipolar disorder and to report the experience of our Teratology Information Service over the past thirteen years in managing women treated with lithium during preconception, pregnancy and breastfeeding. METHODS: This research focuses on a selective review of the literature and a retrospective survey has been carried out on fertile women under lithium treatment who called our service at A. Gemelli University Hospital in Rome from May 2002 to December 2015. RESULTS: A total of 140 women under lithium treatment called our TIS. A complete follow-up has been performed on 34 patients: 29 called during pregnancy and 5 called during preconception. None of the patients called during breastfeeding, while half of the patients were taking concomitant drugs during pregnancy. One major cardiac malformation (hypoplastic left heart syndrome) has been reported. No minor malformations have been detected. Twenty-one patients delivered a living child, with one premature neonate. Two patients underwent voluntary interruption of pregnancy and six patients had early spontaneous abortion. In one patient, intrauterine growth retardation occurred, but with no adverse neonatal outcomes. Four neonates experienced transient respiratory distress at birth. Two children developed mild to severe language delay, but normal motor development. CONCLUSIONS: Lithium treatment in fertile women is a very delicate topic, where risks and benefits of discontinuing therapy when women plan to become pregnant should be accurately evaluated. Thorough peri-conceptional counselling is crucial for the outcome of pregnancy and for maternal health status during preconception, gestation and breastfeeding.
Keywords: lithium; adult; article; autism; bipolar disorder; birth weight; cesarean section; congenital malformation; echocardiography; female; fetus malformation; gestational age; human; intrauterine growth retardation; language delay; major clinical study; neonatal respiratory distress syndrome; newborn; pregnancy; prepregnancy care; retrospective study; teratology; vaginal delivery

Protein loosing enteropathy after fontan procedure - Vijayaraghavan, R.; Ying, T.W. (Medical Journal of Malaysia, 2018)
Fontan and Baudet described the procedure in 1971 and was very useful to improve the quality of life in many complex cyanotic heart diseases. It has gone through various modifications since then to improve the outcome. The mortality was reported as 2.1% and survival rate of at 5 years, 10 years, 15 years and 20 years were 91%, 80%, 73%and 69% respectively. Though it was a useful palliative procedure to improve the quality of life, it has complications which may affect the morbidity and mortality like Protein loosing enteropathy,reduced exercise capacity thromboembolism. The patients with protein losing enteropathy present with Pleural effusion, ascites, and edema and they need periodic replacement of Albumin and frequent reviews and close follow up in the management to reduce the mortality and to improve the quality of life. These complications we come across and they need our support in the management at district level hospitals.
Keywords: albumin; calcium; protein; sildenafil; warfarin; article; ascites; case report; clinical article; computer assisted tomography; cyanotic heart disease; dietary supplement; echocardiography; edema; enteropathy; exercise; feces analysis; follow up; Fontan procedure; Glenn shunt; heart atrium; heart catheterization; heart ventricle septum defect; human; hypoalbuminemia; hypocalcemia; lung artery pressure; lung vein drainage anomaly; male; morbidity; mortality; newborn; outcome assessment; patent ductus arteriosus; pleura effusion; protein losing gastroenteropathy; quality of life; survival rate; thoracocentesis; thromboembolism; transesophageal echocardiography; tricuspid valve disease

Useful References in Pediatric Cardiac Intensive Care: The 2017 Update - Uzark, K.C.; Costello, J.M.; DeSena, H.C.; Thiagajaran, R.; Smith-Parrish, M.; Gist, K.M. (Pediatric Critical Care Medicine, 2018)
Objectives: Pediatric cardiac intensive care continues to evolve, with rapid advances in knowledge and improvement in clinical outcomes. In the past, the Board of Directors of the Pediatric Cardiac Intensive Care Society created and subsequently updated a list of sentinel references focused on the care of critically ill children with congenital and acquired heart disease. The objective of this article is to provide clinicians with a compilation and brief summary of updated and useful references that have been published since 2012. Data Selection: Pediatric Cardiac Intensive Care Society members were solicited via a survey sent out between March 20, 2017, and April 28, 2017, to provide important references that have impacted clinical care. The survey was sent to approximately 523 members. Responses were received from 45 members, of which some included multiple references. Data Extraction: Following review of the list of references, and removing editorials, references were compiled by the first and last author. The final list was submitted to members of the society's Research Briefs Committee, who ranked each publication. Data Synthesis: Rankings were compiled and the references with the highest scores included. Research Briefs Committee members ranked the articles from 1 to 3, with one being highly relevant and should be included and 3 being less important and should be excluded. Averages were computed, and the top articles included in this article. The first (K.C.U.) and last author (K.M.G.) reviewed and developed summaries of each article. Conclusions: This article contains a compilation of useful references for the critical care of children with congenital and acquired heart disease published in the last 5 years. In conjunction with the prior version of this update in 2012, this article may be used as an educational reference in pediatric cardiac intensive care.
Keywords: acquired heart disease; acute kidney failure; advanced practice provider; article; bleeding; cardiopulmonary function; childhood disease; congenital heart disease; coronary care unit; critically ill patient; extracorporeal oxygenation; extubation; glucose homeostasis; heart arrest; heart single ventricle; human; hypervolemia; intensive care nursing; nutrition; palliative therapy; pediatric cardiology; pediatric intensive care unit; perioperative period; postoperative care; preoperative care; priority journal; quality of life; thrombosis; thrombosis prevention

A Multi-Institutional Simulation Boot Camp for Pediatric Cardiac Critical Care Nurse Practitioners - Brown, K.M.; Mudd, S.S.; Hunt, E.A.; Perretta, J.S.; Shilkofski, N.A.; Diddle, J.W.; Yurasek, G.; Bembea, M.; Duval-Arnould, J.; McMillan, K.N. (Pediatric Critical Care Medicine, 2018)
Objectives: Assess the effect of a simulation "boot camp" on the ability of pediatric nurse practitioners to identify and treat a low cardiac output state in postoperative patients with congenital heart disease. Additionally, assess the pediatric nurse practitioners' confidence and satisfaction with simulation training. Design: Prospective pre/post interventional pilot study. Setting: University simulation center. Subjects: Thirty acute care pediatric nurse practitioners from 13 academic medical centers in North America. Interventions: We conducted an expert opinion survey to guide curriculum development. The curriculum included didactic sessions, case studies, and high-fidelity simulation, based on high-complexity cases, congenital heart disease benchmark procedures, and a mix of lesion-specific postoperative complications. To cover multiple, high-complexity cases, we implemented Rapid Cycle Deliberate Practice method of teaching for selected simulation scenarios using an expert driven checklist. Measurements and Main Results: Knowledge was assessed with a pre-/posttest format (maximum score, 100%). A paired-sample t test showed a statistically significant increase in the posttest scores (mean [sd], pre test, 36.8% [14.3%] vs post test, 56.0% [15.8%]; p < 0.001). Time to recognize and treat an acute deterioration was evaluated through the use of selected high-fidelity simulation. Median time improved overall "time to task" across these scenarios. There was a significant increase in the proportion of clinically time-sensitive tasks completed within 5 minutes (pre, 60% [30/50] vs post, 86% [43/50]; p = 0.003] Confidence and satisfaction were evaluated with a validated tool ("Student Satisfaction and Self-Confidence in Learning"). Using a five-point Likert scale, the participants reported a high level of satisfaction (4.7 ± 0.30) and performance confidence (4.8 ± 0.31) with the simulation experience. Conclusions: Although simulation boot camps have been used effectively for training physicians and educating critical care providers, this was a novel approach to educating pediatric nurse practitioners from multiple academic centers. The course improved overall knowledge, and the pediatric nurse practitioners reported satisfaction and confidence in the simulation experience.
Keywords: advanced practice nurse; article; atrioventricular canal; clinical article; clinical assessment; congenital heart disease; curriculum; curriculum development; e-mail; emergency care; forward heart failure; heart injury; high fidelity simulation training; human; hypertensive crisis; hypoplastic left heart syndrome; Likert scale; North America; patient satisfaction; pediatric cardiology; pediatric nurse practitioner; postoperative care; postoperative complication; priority journal; pulmonary hypertension; registered nurse; sedation; task performance; university hospital; work experience

Visuospatial processing in adolescents with critical congenital heart disease: Organization, integration, and implications for academic achievement - Bean Jaworski, J.L.; White, M.T.; DeMaso, D.R.; Newburger, J.W.; Bellinger, D.C.; Cassidy, A.R. (Child Neuropsychology, 2018)
Among the most significant factors affecting quality of life in individuals with critical congenital heart disease (CCHD) are neurodevelopmental challenges, including deficits in visuospatial processing and academic achievement. Few studies have compared outcomes across CCHD subgroups, despite their significant differences in anatomy/physiology and medical/surgical courses. This study compared visuospatial processing abilities using the Developmental Scoring System for the Rey–Osterrieth Complex Figure (DSS-ROCF) across groups of adolescents with CCHD (d-transposition of the great arteries [TGA, n = 139], Tetralogy of Fallot [TOF, n = 68], single-ventricle cardiac anatomy requiring the Fontan operation [SVF, n = 145]) and a group of healthy controls (CTR, n = 111), and examined the validity of visuospatial processing in predicting concurrent academic outcomes. The CCHD subgroups were found to differ in Organization, ps <.001, Structural Accuracy, ps <.001, and Incidental Elements Accuracy scores, ps ≤.008; the post hoc analyses show that the SVF group tended to underperform compared to the other CCHD groups. With respect to academic skills, all CCHD groups scored lower than the CTR group, ps ≤.007; however, the CCHD groups were not different from each other, ps >.23. The regression results showed that the DSS-ROCF Style rating (reflecting integration) accounted for a small yet statistically significant portion of unique variance in “assembled” academic outcomes, over and above the variance already accounted for by DSS-ROCF Organization, p <.01. These findings support the need for comprehensive neuropsychological assessment and monitoring of children and adolescents with CCHD, as well as targeted intervention for organization and integration deficits that may increase their risk for academic underachievement.
Keywords: academic achievement; accuracy; adolescent; adult; article; child; concurrent validity; congenital heart disease; controlled study; critical congenital heart disease; depth perception; Developmental Scoring System; Developmental Scoring System for the Rey Osterrieth Complex Figure; Fallot tetralogy; female; great vessels transposition; heart single ventricle; human; integration; major clinical study; male; multiple regression; organization; post hoc analysis; predictive value; Rey Osterrieth complex figure test; scoring system

Neonatal Brain Injury and Timing of Neurodevelopmental Assessment in Patients With Congenital Heart Disease - Peyvandi, S.; Chau, V.; Guo, T.; Xu, D.; Glass, H.C.; Synnes, A.; Poskitt, K.; Barkovich, A.J.; Miller, S.P.; McQuillen, P.S. (Journal of the American College of Cardiology, 2018)
Background: Brain injury (BI) is reported in 60% of newborns with critical congenital heart disease as white matter injury (WMI) or stroke. Neurodevelopmental (ND) impairments are reported in these patients. The relationship between neonatal BI and ND outcome has not been established. Objectives: This study sought to determine the association between peri-operative BI and ND outcomes in infants with single ventricle physiology (SVP) and d-transposition of the great arteries (d-TGA). Methods: Term newborns with d-TGA and SVP had pre-operative and post-operative brain magnetic resonance imaging and ND outcomes assessed at 12 and 30 months with the Bayley Scales of Infant Development-II. BI was categorized by the brain injury severity score and WMI was quantified by volumetric analysis. Results: A total of 104 infants had follow-up at 12 months and 70 had follow-up at 30 months. At 12 months, only clinical variables were associated with ND outcome. At 30 months, subjects with moderate-to-severe WMI had significantly lower Psychomotor Development Index (PDI) scores (13 points lower) as compared with those with none or minimal WMI for d-TGA and SVP (p = 0.03 and p = 0.05, respectively) after adjusting for various factors. Quantitative WMI volume was likewise associated. Stroke was not associated with outcome. The Bland-Altman limits of agreement for PDI scores at 12 and 30 months were wide (−40.3 to 31.2) across the range of mean PDI values. Conclusions: Increasing burden of WMI is associated with worse motor outcomes at 30 months for infants with critical congenital heart disease, whereas no adverse association was seen between small strokes and outcome. These results support the utility of neonatal brain magnetic resonance imaging in this population to aid in predicting later outcomes and the importance of ND follow-up beyond 1 year of age.
Keywords: article; Bayley Scales of Infant Development; brain injury; clinical assessment; congenital heart disease; controlled study; disease association; female; follow up; great vessels transposition; human; injury scale; major clinical study; male; mental disease; nervous system development; newborn; nuclear magnetic resonance imaging; postoperative period; preoperative evaluation; priority journal; prospective study; Psychomotor Development Index; quantitative analysis; scoring system; single ventricle physiology; time factor; volumetry; white matter injury

Post-arrest therapeutic hypothermia in pediatric patients with congenital heart disease - Cheng, H.H.; Rajagopal, S.K.; Sansevere, A.J.; McDavitt, E.; Wigmore, D.; Mecklosky, J.; Andren, K.; Williams, K.A.; Danehy, A.; Soul, J.S. (Resuscitation, 2018)
Background: While therapeutic hypothermia (TH) is an effective neuroprotective therapy for neonatal hypoxic-ischemic encephalopathy, TH has not been demonstrated to improve outcome in other pediatric populations. Patients with acquired or congenital heart disease (CHD) are at high risk of both cardiac arrest and neurodevelopmental impairments, and therapies are needed to improve neurologic outcome. The primary goal of our study was to compare safety/efficacy outcomes in post-arrest CHD patients treated with TH versus controls not treated with TH. Methods: Patients with CHD treated during the first 18 months after initiation of a post-arrest TH protocol (temperature goal: 33.5 °C) were compared to historical and contemporary post-arrest controls not treated with TH. Post-arrest data, including temperature, safety measures (e.g. arrhythmia, bleeding), neurodiagnostic data (EEG, neuroimaging), and survival were compared. Results: Thirty arrest episodes treated with TH and 51 control arrest episodes were included. The groups did not differ in age, duration of arrest, post-arrest lactate, or use of ECMO-CPR. The TH group's post-arrest temperature was significantly lower than control's (33.6 ± 0.2 °C vs 34.7 ± 0.5 °C, p < 0.001). There was no difference between the groups in safety/efficacy measures, including arrhythmia, infections, chest-tube output, or neuroimaging abnormalities, nor in hospital survival (TH 61.5% vs control 59.1%, p = NS). Significantly more controls had seizures than TH patients (26.1% vs. 4.0%, p = 0.04). Almost all seizures were subclinical and occurred more than 24 h post-arrest. Conclusion: Our data show that pediatric CHD patients who suffer cardiac arrest can be treated effectively and safely with TH, which may decrease the incidence of seizures.
Keywords: fosphenytoin sodium; levetiracetam; midazolam; phenobarbital; topiramate; article; brain ventricle dilatation; child; child safety; childhood disease; clinical article; clinical effectiveness; congenital heart disease; controlled study; electroencephalogram; encephalomalacia; female; heart arrest; heart single ventricle; heart stroke volume; human; hypoxic ischemic encephalopathy; induced hypothermia; infant; infection; male; neuroimaging; neuroprotection; post treatment survival; priority journal; protocol compliance; resuscitation; seizure; sinus bradycardia; subdural hematoma

The five-year survival of children with Down syndrome in Norway 1994–2009 differed by associated congenital heart defects and extracardiac malformations - Brodwall, K.; Greve, G.; Leirgul, E.; Klungsøyr, K.; Holmstrøm, H.; Vollset, S.E.; Øyen, N. (Acta Paediatrica, International Journal of Paediatrics, 2018)
Aim: We investigated the prevalence of Down syndrome in a nationwide birth cohort, focusing on congenital heart defects (CHDs), their associations with extracardiac malformations (ECM) and survival. Methods: National registers were used to identify Norwegian births (1994–2009) and deaths (1994–2014) and updated with hospital diagnoses. We estimated birth defect frequencies in Down syndrome and the general population, the association between CHDs and ECM and hazard ratios for death from different combinations of CHDs and ECM. Results: Down syndrome was found in 1672 of 953 450 births (17.6 per 10 000). Of the 1251 live births (13.3 per 10 000), 58% had CHD and 9% ECM. CHDs were associated with oesophageal atresia (p = 0.02) and Hirschsprung's disease (p = 0.03) but with no other malformations. The five-year survival for Down syndrome increased from 91.8% (1994–1999) to 95.8% (2000–2009) (p = 0.006), and overall survival was 92.0% with CHD and 97.4% without. Compared with Down syndrome children without CHD or ECM, the five-year mortality was similar for those with nonsevere CHDs, without or with ECM, but 4–7 times higher in those with severe CHDs without ECM and 13–28 times higher in those with severe CHDs and ECM. Conclusion: Down syndrome childhood survival improved, but mortality remained high with severe CHDs and extracardiac defects.
Keywords: aortic valve stenosis; article; atrioventricular septal defect; cardiovascular mortality; child; childhood mortality; congenital heart malformation; congenital malformation; controlled study; disease association; disease severity; Down syndrome; esophagus atresia; extracardiac malformation; Fallot tetralogy; heart left ventricle outflow tract obstruction; heart right ventricle double outlet; Hirschsprung disease; human; hypoplastic left heart syndrome; ICD-10; ICD-9; live birth; lung vein drainage anomaly; major clinical study; maternal age; overall survival; prevalence; priority journal; stillbirth

Delayed puberty and abnormal anthropometry and its associations with quality of life in young Fontan survivors: A multicenter cross-sectional study - Menon, S.C.; Al-Dulaimi, R.; McCrindle, B.W.; Goldberg, D.J.; Sachdeva, R.; Goldstein, B.H.; Seery, T.; Uzark, K.C.; Chelliah, A.; Butts, R.; Henderson, H.; Johnson, T.; et al. (Congenital Heart Disease, 2018)
Introduction: We sought to evaluate the prevalence of delayed puberty and abnormal anthropometry and its association with quality of life (QoL) in young Fontan survivors. Methods: This was a cross-sectional study at 11 Pediatric Heart Network centers. Demographic and clinical data, anthropomety, and Tanner stage were collected. Anthropometric measurements and pubertal stage were compared to US norms. QoL was assessed using Pediatric Quality of Life inventory (PedsQL). Mixed effects regression modeling adjusting for clustering by center was used to evaluate factors associated with abnormal anthropometry and delayed puberty and associations with QoL. Results: Of the 299 subjects, 42% were female. The median enrollment age was 13.9 years, and the median age at Fontan was 3 years. Fontan survivors had a higher prevalence of short stature relative to normative data (20% vs 5%, P <.0001) and an increased prevalence of abnormal BMI (16% vs 10%, P <.0001) (low [43%] and high [57%]). Fontan subjects, both males (58%) and females (58%), had a delay of 1.5‒2 years in ≥1 Tanner stage parameter compared to normal population. There was no association between delayed puberty and QoL. Abnormal anthropometry was associated with lower overall (62.3 ± 17.3 vs 72.5 ± 16.6; P <.001) and physical appearance scores (72.2 ± 27.4 vs 79.8 ± 21.5; P <.01). Lower exercise capacity was associated with abnormal anthropometry and >2 surgeries before Fontan was associated with delayed puberty. Lower family income (<$25 000) and hypoplastic left heart syndrome were associated with lower QoL. Conclusion: Compared to the normal population, Fontan survivors have high prevalence of short stature, abnormal BMI and delayed puberty. Abnormal anthropometry, but not delayed puberty, was associated with lower overall QoL and perceived physical appearance scores. Routine screening for abnormal anthropometry, especially in HLHS and in lower socioeconomic status families, should be considered to allow interventions, which might ameliorate the negative psychosocial impact.
Keywords: adolescent; anthropometry; article; body mass; child; controlled study; cross-sectional study; delayed puberty; disease severity; exercise; family income; female; Fontan procedure; human; hypoplastic left heart syndrome; major clinical study; male; multicenter study; New York Heart Association class; oxygen consumption; Pediatric Quality of Life Inventory; physical appearance; quality of life; short stature; social status; survivor; United States

Respiratory Training Late After Fontan Intervention: Impact on Cardiorespiratory Performance - Ait Ali, L.; Pingitore, A.; Piaggi, P.; Brucini, F.; Passera, M.; Marotta, M.; Cadoni, A.; Passino, C.; Catapano, G.; Festa, P. (Pediatric Cardiology, 2018)
Fontan palliation allows patients with “single ventricle” circulation to reach adulthood with an acceptable quality of life, although exercise tolerance is significantly reduced. To assess whether controlled respiratory training (CRT) increases cardiorespiratory performance. 16 Adolescent Fontan patients (age 17. 5 ± 3.8 years) were enrolled. Patients were divided into CRT group (n = 10) and control group (C group, n = 6). Maximal cardiopulmonary test (CPT) was repeated at the end of CRT in the CRT group and after an average time of 3 months in the C group. In the CRT group a CPT endurance was also performed before and after CRT. In the CRT group there was a significant improvement in cardiovascular and respiratory response to exercise after CRT. Actually, after accounting for baseline values, the CRT group had decreased breathing respiratory reserve (− 15, 95% CI −22.3 to − 8.0, p = 0.001) and increased RR peak (+ 4.8, 95% CI 0.7–8.9, p = 0.03), VE peak (+ 13.7, 95% CI 5.6–21.7, p = 0.004), VO2 of predicted (+ 8.5, 95% CI 0.1–17.0, p = 0.05), VO2 peak (+ 4.3, 95% CI 0.3 to 8.2, p = 0.04), and VO2 workslope (+ 1.7, 95% CI 0.3–3.1, p = 0.02) as compared to the control group. Moreover, exercise endurance time increased from 8.45 to 17.7 min (p = 0.01). CRT improves cardiorespiratory performance in post-Fontan patients leading to a better aerobic capacity.
Keywords: adolescent; aerobic capacity; article; breathing exercise; cardiopulmonary test; cardiorespiratory fitness; clinical article; clinical effectiveness; controlled respiratory training; controlled study; endurance training; female; Fontan procedure; human; lung function test; male; outcome assessment; patient safety; prediction; repeat procedure

A randomised trial of early palliative care for maternal stress in infants prenatally diagnosed with single-ventricle heart disease - Hancock, H.S.; Pituch, K.; Uzark, K.; Bhat, P.; Fifer, C.; Silveira, M.; Yu, S.; Welch, S.; Donohue, J.; Lowery, R.; Aiyagari, R. (Cardiology in the Young, 2018)
Children with single-ventricle disease experience high mortality and complex care. In other life-limiting childhood illnesses, paediatric palliative care may mitigate maternal stress. We hypothesised that early palliative care in the single-ventricle population may have the same benefit for mothers. In this pilot randomised trial of early palliative care, mothers of infants with prenatal single-ventricle diagnoses completed surveys measuring depression, anxiety, coping, and quality of life at a prenatal visit and neonatal discharge. Infants were randomised to receive early palliative care - structured evaluation, psychosocial/spiritual, and communication support before surgery - or standard care. Among 56 eligible mothers, 40 enrolled and completed baseline surveys; 38 neonates were randomised, 18 early palliative care and 20 standard care; and 34 postnatal surveys were completed. Baseline Beck Depression Inventory-II and State-Trait Anxiety Index scores exceeded normal pregnant sample scores (mean 13.76±8.46 versus 7.0±5.0 and 46.34±12.59 versus 29.8±6.35, respectively; p=0.0001); there were no significant differences between study groups. The early palliative care group had a decrease in prenatal to postnatal State-Trait Anxiety Index scores (-7.6 versus 0.3 in standard care, p=0.02), higher postnatal Brief Cope Inventory positive reframing scores (p=0.03), and a positive change in PedsQL Family Impact Module communication and family relationships scores (effect size 0.46 and 0.41, respectively). In conclusion, these data show that mothers of infants with single-ventricle disease experience significant depression and anxiety prenatally. Early palliative care resulted in decreased maternal anxiety, improved maternal positive reframing, and improved communication and family relationships.
Keywords: NCT02462434; adult; anxiety; article; Beck Depression Inventory; clinical article; cohort analysis; controlled study; coping behavior; depression; early intervention; family relation; female; heart single ventricle; hospital discharge; human; infant; interpersonal communication; male; maternal stress; palliative therapy; perinatal period; pilot study; prenatal diagnosis; psychosocial care; quality of life; randomized controlled trial; spiritual care; State Trait Anxiety Inventory

Cerebral Blood Flow Following Hybrid Stage I Palliation in Infants with Hypoplastic Left Heart Syndrome - Cheatham, S.L.; Chisolm, J.L.; O’Brien, N. (Pediatric Cardiology, 2018)
Hypoplastic left heart syndrome (HLHS) palliation may result in altered cerebral blood flow with subsequent neurodevelopmental implications. The purpose of the study was to assess blood flow in the middle cerebral artery (MCA) and investigate the relationship with early neurodevelopmental outcomes in infants with HLHS after hybrid stage I. Transcranial Doppler (TCD) was performed to obtain peak systolic, end-diastolic, and mean velocities, as well as pulsatility index of the MCA in infants with HLHS (n = 18) at baseline and at 2, 4, and 6 months of age. Developmental assessment was performed at 6 months of age. Results of TCD and development were compared to healthy control subjects (n = 6) and normative data. Overall, peak systolic velocity (p = 0.0031), end-diastolic velocity (p < 0.0001), and mean velocity (p < 0.0001) were significantly lower and pulsatility index (p = 0.0011) significantly higher in the HLHS group compared to the control group. A significant increase in change over time was noted for peak systolic velocity (p < 0.0016) and mean velocity (p < 0.0046). There was no significant correlation between TCD variables and development scores. TCD values in 5–6 months old infants with HLHS who undergo hybrid stage I palliation had consistently lower blood flow velocities than control infants; however, pulsatility index was slightly higher. No correlation between TCD measurements and measures of cognitive, language, and motor skills were noted.
Keywords: Companion III; ultrasound transducer; artery blood flow; article; blood flow velocity; brain blood flow; brain perfusion; child development; clinical article; cognitive development; controlled study; female; gestational age; head circumference; heart surgery; heart ventricle enddiastolic pressure; human; hypoplastic left heart syndrome; language development; longitudinal study; male; middle cerebral artery; motor performance; newborn; palliative therapy; prospective study; pulsatility index; systolic blood pressure; transcranial Doppler ultrasonography; treatment planning; Companion III

Teeth infection may "shunt" through Fontan in high-altitude conditions - Sierra, J.D.C.; Mestra, C.F.; Nieto, J.C.G.; Dumit, M.R.; García-Torres, A. (Annals of Translational Medicine, 2018)
The Fontan surgery involves the creation a conduit between the inferior vena cava and the right pulmonary artery. This conduit has a small fenestration that shunts the blood from right to left in case the pulmonary blood flow is limited; namely, if the pulmonary vascular resistance (PVR) is increased then the shunt is increased. Bacteria may bypass the pulmonary circulation and easily get access to the systemic circulation (bacteremia). We report the case of a patient that underwent Fontan surgery in 2010 and remained in a high-altitude city for 7 years, during this time he was asymptomatic until 2017 when he developed a brain abscess due to Streptococcus gordonii, a pathogen of dental plaque. Since high-altitude may raise PVR in response to reduction in the partial pressure of oxygen, we conclude that the long-term outcome of increased altitude on Fontan hemodynamics can lead to the shunt of teeth flora and consequently leading to severe infections.
Keywords: C reactive protein; cefepime; ceftriaxone; erythromycin; furosemide; penicillin derivative; spironolactone; vancomycin; warfarin; altitude; antibiotic sensitivity; article; bacterium identification; brain abscess; case report; child; clinical article; computer assisted tomography; craniotomy; dental pulp capping; depersonalization; deterioration; disease duration; disorientation; echocardiography; erythrocyte sedimentation rate; fever; Fontan procedure; general anesthesia; headache; hemodynamics; human; incubation time; international normalized ratio; leukocyte count; lung vascular resistance; male; medical history; minimum inhibitory concentration; physical examination; protein blood level; risk factor; school child; Streptococcus gordonii; tooth extraction; tooth infection; tooth plaque; tricuspid valve atresia; vomiting

Functional outcome in contemporary children with total cavopulmonary connection – Health-related physical fitness, exercise capacity and health-related quality of life - Hock, J.; Reiner, B.; Neidenbach, R.C.; Oberhoffer, R.; Hager, A.; Ewert, P.; Müller, J. (International Journal of Cardiology, 2018)
Objective: Children and adolescents with an univentricular heart after total cavopulmonary connection (TCPC) have functional impairments. This study assesses health-related physical fitness (HRPF) and exercise capacity, as well as their relation to health-related quality of life (HRQoL) in patients with an univentricular heart after total-pulmonary connection (TCPC). Patients and methods: Between July 2014 and October 2016 a total of 78 children and adolescents with TCPC (12.0 ± 3.2 years, 21 female) performed a motor test including five tasks for strength and flexibility during their routine follow-up appointment. They also underwent a symptom limited cardio-pulmonary exercise test and filled in a HRQoL questionnaire (KINDL-R). Patients' data were compared to a recent sample of healthy children (n = 1650, 12.6 ± 2.4 years, 49% female). Results: Multivariable regressions corrected for sex, age and BMI showed that TCPC patients achieved 12.4 repetitions of curl-ups (p < 0.001) and 2.6 push-ups (p = 0.010) less than healthy counterparts. They had impairments in trunk (− 8.5 cm; p < 0.001), shoulder (− 7.5 cm; p < 0.001) and lower limb flexibility (− 4.7 cm; p < 0.001). Peak oxygen uptake was reduced to 34.8 ± 7.5 ml/min/kg and 77.7% respectively, compared to peers (p < 0.001). Ventilatory efficiency was also impaired (healthy: 27.5 ± 2.9 vs. TCPC: 31.6 ± 3.3; p < 0.001). HRQoL did not differ significantly (p = 0.233). Conclusions: Children and adolescents with TCPC still present impaired HRPF and exercise capacity whereas HRQoL is similar to healthy peers. Since low HRPF may yield to worse motor competence and exercise capacity, early screening for HRPF and early treatment, if indicated, is recommended.
Keywords: oxygen; adolescent; age; article; body mass; cardiopulmonary exercise test; cavopulmonary connection; child; congenital heart disease; controlled study; exercise; female; fitness; follow up; human; lower limb; major clinical study; male; oxygen consumption; pediatrics; priority journal; quality of life; sex difference; shoulder; trunk

A novel temporal pattern of childhood cerebral X-linked adrenoleukodystrophy - Turco, E.C.; Ormitti, F.; Andreolli, A.; Barsacchi, M.; Facini, C.; Pisani, F. (Brain and Development, 2018)
We report a 9-year-old boy, with childhood cerebral X-linked adrenoleukodystrophy (CCALD), presenting with an episode of loss of consciousness, fixed gaze, hypotonia and vomit with spontaneous resolution and post-ictal sleep. Behavioural impairment has been observed since the previous five months. Magnetic Resonance Images (MRI) revealed isolated bilateral, symmetric, confluent temporal white matter lesions involving also corticospinal tracts, with sparing of the parieto-occipital and frontal white matter. This report outlines an atypical neuroradiological localization of X-linked adrenoleukodystrophy and neuropsychological findings not specifically related to the brain involvement seen at the MRI.
Keywords: anticonvulsive agent; very long chain fatty acid; adrenoleukodystrophy; anticonvulsant therapy; article; case report; child; childhood cerebral X linked adrenoleukodystrophy; childhood disease; clinical article; consciousness disorder; deterioration; diet therapy; electroencephalogram; epilepsy; executive function; human; hyperactivity; intelligence quotient; male; medical history; muscle hypotonia; neurologic examination; neuropsychological test; nuclear magnetic resonance imaging; priority journal; pulmonary artery stenosis; school child; tricuspid valve atresia; vomiting; Wechsler intelligence scale for children; white matter lesion; Wisconsin Card Sorting Test

Physical activity perceptions and behaviors among young adults with congenital heart disease: A mixed-methods study - McKillop, A.; McCrindle, B.W.; Dimitropoulos, G.; Kovacs, A.H. (Congenital Heart Disease, 2018)
Objective: A physically active lifestyle can help maintain positive physical and psychosocial health outcomes among adults with congenital heart disease (CHD). This study explored the physical activity perceptions and behaviors among young adults with CHD. Design: This was a cross-sectional, mixed-methods study that included objectively measured physical activity assessment (accelerometer), individual semistructured interviews, and psychosocial questionnaires. Results: Fifteen participants (67% male; 21 ± 3 years old) with moderate (n = 10) or complex (n = 5) CHD were recruited from an outpatient adult CHD clinic. Participants accumulated 26 ± 16 minutes of moderate-to-vigorous physical activity per day, and reported a high quality of life, moderate self-efficacy for exercise, and low cardiac-focused anxiety. Qualitative data indicated that participants reported more positive perceptions toward activity if their family members encouraged physical activity participation, including siblings that engaged in physical activity alongside participants. Participants described parents as supportive rather than overprotective. Activity precautions were perceived by participants as being instructions from cardiologists rather than restrictions by parents. Participants described some physical limitations compared to peers, but managed challenges by either working within their limitations or choosing activities that met their expectations and/or in which they could fully participate. Participants often described childhood physical activity in the context of school, physical education, and organized sports. Whereas physical activity in childhood was viewed as recreational, the cardiac health-promoting aspects became more prominent in adulthood. Activities performed during one's employment were considered sufficient to meet physical activity recommendation levels, and participants reported limited time and/or energy to participate in activity outside of work. Conclusions: The influence of family appeared to help participants adopt a positive perception toward activity participation in childhood that was carried forward to young adulthood. Future clinical work should target adolescents with CHD with less social supports and/or negative perceptions toward physical activity.
Keywords: accelerometer; wGT3X; adult; anxiety assessment; aortic coarctation; article; atrioventricular septal defect; behavior assessment; bicuspid aortic valve; cardiac anxiety; Cardiac Anxiety Questionnaire; clinical article; congenital heart disease; cross-sectional study; employment; exercise; Fallot tetralogy; family attitude; female; health promotion; human; hypoplastic left heart syndrome; male; parental attitude; physical activity; physical education; priority journal; quality of life; Readiness to Change questionnaire; recreation; Self Efficacy for Exercise Scale; semi structured interview; sport; visual analog scale; young adult; wGT3X

Can endurance training improve physical capacity and quality of life in young Fontan patients? - Hedlund, E.R.; Lundell, B.; Soderstrom, L.; Sjoberg, G. (Cardiology in the Young, 2018)
Objective Children after Fontan palliation have reduced exercise capacity and quality of life. Our aim was to study whether endurance training could improve physical capacity and quality of life in Fontan patients. Methods Fontan patients (n=30) and healthy age- And gender-matched control subjects (n=25) performed a 6-minute walk test at submaximal capacity and a maximal cycle ergometer test. Quality of life was assessed with Pediatric Quality of Life Inventory Version 4.0 questionnaires for children and parents. All tests were repeated after a 12-week endurance training programme and after 1 year. Results Patients had decreased submaximal and maximal exercise capacity (maximal oxygen uptake 35.0±5.1 ml/minute per·kg versus 43.7±8.4 ml/minute·per·kg, p<0.001) and reported a lower quality of life score (70.9±9.9 versus 85.7±8.0, p<0.001) than controls. After training, patients improved their submaximal exercise capacity in a 6-minute walk test (from 590.7±65.5 m to 611.8±70.9 m, p<0.05) and reported a higher quality of life (p<0.01), but did not improve maximal exercise capacity. At follow-up, submaximal exercise capacity had increased further and improved quality of life was sustained. The controls improved their maximal exercise capacity (p<0.05), but not submaximal exercise capacity or quality of life after training. At follow-up, improvement of maximal exercise capacity was sustained. Conclusions We believe that an individualised endurance training programme for Fontan patients improves submaximal exercise capacity and quality of life in Fontan patients and the effect on quality of life appears to be long-lasting.
Keywords: bicycle ergometer; carbon dioxide; oxygen; adolescent; article; cardiopulmonary exercise test; child; controlled study; endurance training; exercise; female; human; major clinical study; male; muscle weakness; oxygen consumption; Pediatric Quality of Life Inventory; physical capacity; quality of life; questionnaire; scoring system; self concept; six minute walk test; social psychology

“Will she live a long happy life?” Parents' concerns for their children with Fontan circulation - du Plessis, K.; Peters, R.; King, I.; Robertson, K.; Mackley, J.; Maree, R.; Stanley, T.; Pickford, L.; Rose, B.; Orchard, M.; Stewart, H.; d'Udekem, Y. (IJC Heart and Vasculature, 2018)
Background: Families of children at the worst end of the congenital heart disease endure a significant burden which is often not clearly delineated in the clinical literature. We examined the greatest concerns of parents whose children have a Fontan circulation. Methods: Parents (N = 107) of children in the Australian and New Zealand Fontan Registry completed online surveys with open-ended and closed questions. A qualitative method approach incorporating thematic analyses was used. Results: The greatest concerns for parents of a child with a Fontan circulation were centered on fear of death for their child and psychosocial well-being, followed by lesser themes around anti-coagulation use, pregnancy and financial burdens. Conclusions: Fear of death and the psychological well-being of their children were the main parental concerns. It highlights the need to clearly communicate information on outcomes to families, and the need for family-focused psychological interventions to improve the psychosocial functioning of both parents and young people.
Keywords: warfarin; article; bone density; child; emotional stability; exhaustion; fatigue; Fontan procedure; human; international normalized ratio; life expectancy; major clinical study; mental health; pregnancy; priority journal; quality of life; social psychology

Posterior spinal fusion for scoliosis after Fontan procedure: A case series - Uehara, M.; Takahashi, J.; Akazawa, Y.; Kuraishi, S.; Ikegami, S.; Futatsugi, T.; Oba, H.; Kato, H. (Journal of Orthopaedic Science, 2018)
Background: As the surgical treatment of scoliosis after a Fontan procedure is very challenging due to the risk of various perioperative complications, case reports are scarce. We herein describe three patients who were successfully treated for scoliosis following a Fontan procedure and discuss their clinical and radiological outcomes. Methods: We retrospectively reviewed three cases of scoliosis treated by posterior spinal fusion after a Fontan procedure. Results: Mean preoperative major curve Cobb angle was 83.7°, mean surgical time was 233.0 min, and mean blood loss was 1167 g. The mean correction rate of the major curve was 48.0%. Surgical outcome as evaluated by Scoliosis Research Society-22 patient questionnaires revealed acceptable results without any severe complications. Conclusions: Corrective surgery for scoliosis after a Fontan procedure becomes a stronger option if cardiac insufficiency is prevented during the perioperative period and a conservative plan is carried out with minimal invasiveness and operation time.
Keywords: adolescent; article; child; clinical article; Cobb angle; conservative treatment; disease severity; female; Fontan procedure; forced vital capacity; human; major clinical study; male; mental health; operation duration; outcome assessment; perioperative period; peroperative complication; posterior spinal fusion; postoperative period; retrospective study; risk factor; school child; scoliosis; self concept; spine fusion; surgical patient

Quality of life and sexual well-being in patients with a Fontan circulation: An explorative pilot study with a mixed method design - Wolff, D.; van de Wiel, H.B.M.; de Muinck Keizer, M.E.; van Melle, J.P.; Pieper, P.G.; Berger, R.M.F.; Ebels, T.; Weijmar Schultz, W.C.M. (Congenital Heart Disease, 2018)
Objective: To get an impression of the quality of life (QOL) and sexual well-being in the Fontan population, and to generate hypotheses for future research. Methods: For this cross-sectional pilot study, questionnaires regarding health-related QOL, sexual function and fertility/pregnancy were completed by 21 patients with a Fontan circulation >16 years old, followed at the University Medical Center Groningen, the Netherlands. Semi-structured qualitative interviews were conducted in 8 patients. Results: Fontan patients scored significantly lower on general health than their healthy peers (t(19)=-3.0, P =.008), whereas their scores on other QOL domains and sexual well-being were comparable to normal values. During childhood, most patients experienced physical limitations and the feeling of being an outsider, and frequently faced bullying. Regarding sexual well-being, large interindividual differences were noted. Four interviewed patients (25-30 years) reported a good sexual well-being, whereas the other interviewed patients (33-47 years) reported erectile dysfunction, low self-esteem and avoidance of sexual intercourse. Both the QOL domains mental health and role restrictions due to emotional problems were associated with female avoidance (P =.083, respectively, P =.089) and dyspareunia (P = ns respectively P =.094). In males, role restrictions due to physical problems and health change were related to sexual dissatisfaction (P =.056) respectively nonsensuality (P =.025). Conclusions: Overall, Fontan patients have a relatively preserved quality of life and sexual wellbeing but face more social isolation and bullying during childhood/adolescence than their healthy peers. Sexual problems were mainly associated with physical limitations in males and with psychosocial limitations in females. Finally, sexual dysfunction was more common in older Fontan patients, and future research has to clarify whether progressive attrition of the Fontan circulation affects the patients' QOL and sexual well-being.
Keywords: adult; article; bullying; clinical article; cross-sectional study; dyspareunia; erectile dysfunction; female; Fontan procedure; human; male; Netherlands; pilot study; pregnancy; priority journal; quality of life; self esteem; semi structured interview; sexual function; sexual intercourse; sexual satisfaction; sexual wellbeing; social isolation; wellbeing

Transcoronary cell infusion with the stop-flow technique in children with single-ventricle physiology - Eitoku, T.; Baba, K.; Kondou, M.; Kurita, Y.; Fukushima, Y.; Hirai, K.; Ohtsuki, S.; Ishigami, S.; Sano, S.; Oh, H. (Pediatrics International, 2018)
Background: Almost all reports on cardiac regeneration therapy have referred to adults, and only a few have focused on transcoronary infusion of cardiac progenitor cells using the stop-flow technique in children. Methods: Intracoronary autologous cardiosphere-derived cell (CDC) transfer was conducted at Okayama University as a phase 1 clinical trial for seven patients with hypoplastic left heart syndrome between January 2011 and December 2012, and as a phase 2 clinical trial for 34 patients with single-ventricle physiology between July 2013 and March 2015. Results: A total of 41 patients with single-ventricle physiology underwent transcoronary infusion of CDC with the stop-flow technique. The median age was 33 months (range, 5–70 months) and the median weight was 10.1 kg (range, 4.1–16.0 kg). Transient adverse events occurred during the procedure, including ST-segment elevation or depression, hypotension, bradycardia, and coronary artery vasospasm. All patients completely recovered. There were no major procedure-related adverse events. In this study, transcoronary infusion of CDC using the stop-flow technique was successfully completed in all patients. Conclusion: Transcoronary infusion of CDC using the stop-flow technique in children is a feasible and safe procedure.
Keywords: NCT01273857; NCT01829750; 5F Launcher; guiding catheter; imaging system; INFX 8000V Biplane; Kudos; adverse event; age; article; balloon occlusion; blood pressure; body weight; bradycardia; cardiac muscle cell; cardiosphere derived cell; cardiovascular function; cardiovascular procedure; cell therapy; cell transfer; child; clinical article; controlled study; coronary artery spasm; depression; female; heart rate; heart single ventricle; human; hypoplastic left heart syndrome; hypotension; male; patient safety; priority journal; ST segment elevation; stop flow technique; transcoronary cell infusion; treatment duration; treatment outcome; 5F Launcher; INFX 8000V Biplane; Kudos

Array comparative genomic hybridization as the first-line investigation for neonates with congenital heart disease: Experience in a single tertiary center - Choi, B.G.; Hwang, S.-K.; Kwon, J.E.; Kim, Y.H. (Korean Circulation Journal, 2018)
Background and Objectives: The purpose of the present study was to investigate the advantages and disadvantages of verifying genetic abnormalities using array comparative genomic hybridization (a-CGH) immediately afer diagnosis of congenital heart disease (CHD). Methods: Among neonates under the age of 28 days who underwent echocardiography from January 1, 2014 to April 30, 2016, neonates whose chromosomal and genomic abnormalities were tested using a-CGH in cases of an abnormal fnding on echocardiography were enrolled. Results: Of the 166 patients diagnosed with CHD, 81 underwent a-CGH and 11 patients (11/81, 13.5%) had abnormal fndings on a-CGH. 22q11.2 deletion syndrome was the most common (4/11, 36.4%). On the frst a-CGH, 4 patients were negative (4/81, 5%). Three of them were fnally diagnosed with Williams syndrome using fluorescent in situ hybridization (FISH), 1 patient was diagnosed with Noonan syndrome through exome sequencing. All of them exhibited difluse pulmonary artery branch hypoplasia, as well as increased velocity of blood flow, on repeated echocardiography. Five patients started rehabilitation therapy at mean 6 months old age in outpatient clinics and epilepsy was diagnosed in 2 patients. Parents of 2 patients (22q11.2 deletion syndrome and Patau syndrome) refused treatment due to the anticipated prognosis. Conclusions: Screening tests for genetic abnormalities using a-CGH in neonates with CHD has the advantage of early diagnosis of genetic abnormality during the neonatal period in which there is no obvious symptom of genetic abnormality. However, there are disadvantages that some genetic abnormalities cannot be identifed on a-CGH.
Keywords: aortic coarctation; artery dysplasia; article; blood flow velocity; chromosome aberration; chromosome deletion 22q11; comparative genomic hybridization; congenital heart disease; controlled study; echocardiography; epilepsy; Fallot tetralogy; fluorescence in situ hybridization; genetic disorder; heart ventricle septum defect; human; hypoplastic left heart syndrome; major clinical study; newborn; Noonan syndrome; outpatient department; prognosis; pulmonary artery; pulmonary valve atresia; rehabilitation care; tertiary care center; trisomy 13; whole exome sequencing; Williams Beuren syndrome

Regional brain gray matter changes in adolescents with single ventricle heart disease - Singh, S.; Kumar, R.; Roy, B.; Woo, M.A.; Lewis, A.; Halnon, N.; Pike, N. (Neuroscience Letters, 2018)
Adolescents with single ventricle heart disease (SVHD) show autonomic, mood, and cognitive deficits, indicating aberrations in brain areas that regulate these functions. However, the gray matter integrity in autonomic, mood, and cognitive control sites is unclear. We examined regional brain gray matter changes, using high-resolution T1-weighted images (3.0-T magnetic resonance scanner) with voxel based morphometry procedures, as well as mood and cognitive functions in SVHD (n = 18; age, 15.7 ± 1.1 years; male, 10) and controls (n = 31; age, 16.0 ± 1.1 years; male, 17). High-resolution T1-weighted images were realigned, gray matter tissue type partitioned, normalized to a common space, smoothed, and compared between groups (analysis of covariance; covariates, age and gender). The mood and cognitive scores were compared between groups using independent samples t-tests. SVHD subjects showed significantly altered mood and cognitive functions over controls. Significantly reduced gray matter emerged in multiple brain areas, including the thalamus, caudate nuclei, putamen, insula, prefrontal, post-central and precentral gyrus, occipital gyrus, para-hippocampal gyrus, temporal gyrus, and cerebellar sites in SVHD over controls. SVHD subjects show compromised gray matter integrity in autonomic, mood and cognitive control sites. The findings indicate that frequent deficits found in SVHD subjects have a brain structural basis in the condition.
Keywords: Manetom Tim Trio and Prisma; nuclear magnetic resonance scanner; adolescent; article; brain region; caudate nucleus; cerebellum; clinical article; cognition; controlled study; executive function; female; gray matter; heart single ventricle; human; insula; male; mood change; occipital gyrus; parahippocampal gyrus; prefrontal cortex; primary motor cortex; priority journal; putamen; temporal gyrus; temporal lobe; thalamus; voxel based morphometry; Manetom Tim Trio and Prisma

Prevalence of Coronary Artery Disease Risk Factors and Metabolic Syndrome in Children with Heart Disease - Ware, A.L.; Young, P.C.; Weng, C.; Presson, A.P.; Minich, L.L.A.; Menon, S.C. (Pediatric Cardiology, 2018)
Children with acquired and congenital heart disease (CHD) are increasingly surviving to adulthood. Our aim was to determine the prevalence of coronary artery disease (CAD) risk factors in children at known risk for early CAD or with severe CHD. We recruited children (8–19 years) at risk for early CAD—Kawasaki disease (KD, N = 36) and coarctation (69) or severe CHD: > 1 cardiopulmonary bypass surgery (60), single ventricle (15), prosthetic valves (13). Anthropometric measurements, blood pressure, and fasting lipid data were compared with summaries from National Health and Nutrition Examination Survey (NHANES) publications (1999–2012). Relative risk (RR) ratios were calculated based on age classification and pooled to obtain overall RR. Of 174 subjects, 106 were male (61%) and 138 (79%) had CHD. Compared to NHANES data, hypertension and low HDL were higher in the study cohort [RR 11.7 (CI 6.34–21.6), p < 0.001; and 1.79 (CI 1.36–2.35). p < 0.001] and obesity and elevated total cholesterol were lower [RR 0.59 (CI 0.37–0.96), p = 0.03; and 0.42 (CI 0.19–0.95), p = 0.04]. Elevated non-HDL was similar between groups. Age category had similar RR for all CAD risk factors. Eight subjects had metabolic syndrome. Risk factors were similar between KD versus CHD subgroups. Both coarctation and non-coarctation subjects had increased RR for hypertension. Hypertension is the most common risk factor for children at risk of early CAD and severe CHD. Metabolic syndrome is rare. These patients should be screened and treated for hypertension and current recommendations for universal lipid screening are adequate for follow-up.
Keywords: heart valve prosthesis; glucose; article; body height; body mass; body weight; cardiovascular risk; cholesterol blood level; congenital heart disease; coronary artery disease; disease severity; family history; female; glucose blood level; heart single ventricle; human; hypercholesterolemia; hypertension; insulin dependent diabetes mellitus; major clinical study; male; metabolic syndrome X; mucocutaneous lymph node syndrome; obesity; prevalence; puberty; risk assessment; risk factor; smoking; systolic blood pressure; waist circumference

Oxidation Reduction Potential (ORP) is Predictive of Complications Following Pediatric Cardiac Surgery - Schmidt, A.E.; Gore, E.; Henrichs, K.F.; Conley, G.; Dorsey, C.; Bjugstad, K.B.; Refaai, M.A.; Blumberg, N.; Cholette, J.M. (Pediatric Cardiology, 2018)
Oxidation reduction potential (ORP) or Redox is the ratio of activity between oxidizers and reducers. Oxidative stress (OS) can cause cellular injury and death, and is important in the regulation of immune response to injury or disease. In the present study, we investigated changes in the redox system as a function of cardiopulmonary bypass (CPB) in pediatric patients. 664 plasma samples were collected from 162 pediatric patients having cardiac surgery of various CPB times. Lower ORP values at 12 h post-CPB were associated with poor survival rate (mean ± SD 167 ± 20 vs. 138 ± 19, p = 0.005) and higher rate of thrombotic complications (153 ± 21 vs. 168 ± 20, p < 0.008). Similarly, patients who developed infections had lower ORP values at 6 h (149 ± 19 vs. 160 ± 22, p = 0.02) and 12 h (156 ± 17 vs. 168 ± 21, p = 0.004) post-CPB. Patients that developed any post-operative complication also had lower 6 h (149 ± 17 vs. 161 ± 23, p = 0.002) and 12 h (157 ± 18 vs. 170 ± 21, p = 0.0007) post-CPB ORP values. Free hemoglobin and IL-6, IL-10, and CRP were not associated with ORP levels. However, higher haptoglobin levels preoperatively were protective against decreases in ORP. Decreased ORP is a marker for poor outcome and predictive of post-operative thrombosis, infection, and other complications in critically ill pediatric cardiac surgery patients. These results suggest that redox imbalance and OS may contribute to the risk of complications and poor outcome in pediatric CBP patients. Haptoglobin may be a marker for increased resilience to OS in this population.
Keywords: NCT00693498; C reactive protein; haptoglobin; hemoglobin; interleukin 10; interleukin 6; adolescent; article; bleeding; cardiopulmonary bypass; child; complete heart block; controlled study; cyanotic heart disease; female; heart single ventricle; heart surgery; human; hypoxia; infant; junctional ectopic tachycardia; major clinical study; male; newborn; oxidation reduction potential; pediatric surgery; postoperative complication; predictive value; preoperative period; surgical infection; survival rate; thrombosis

A compromised maternal vitamin D status is associated with congenital heart defects in offspring - Koster, M.P.H.; van Duijn, L.; Krul-Poel, Y.H.M.; Laven, J.S.; Helbing, W.A.; Simsek, S.; Steegers-Theunissen, R.P.M. (Early Human Development, 2018)
Background Interactions between genetic and environmental factors, including modifiable maternal nutrition and lifestyle, play a significant role in the pathogenesis of most congenital heart defects (CHD). The aim of this study was to investigate associations between periconceptional maternal vitamin D status and the prevalence of CHD in offspring. Methods A case-control study was performed in 345 mothers of a child with CHD and 432 mothers of a child without CHD from four tertiary hospitals in the Netherlands between 2003 and 2005. Approximately 15 months after pregnancy mothers filled out questionnaires regarding general characteristics and periconceptional lifestyle. Maternal blood was obtained to determine serum 25-hydroxyvitamin D and lipid concentrations. The 25-hydroxyvitamin D concentration was stratified into a deficient < 50 nmol/l, moderate 50–75 nmol/l and adequate > 75 nmol/l status. Logistic regression was performed to study associations between vitamin D status and CHD risk, adjusted for maternal age, body mass index, ethnicity, smoking and total cholesterol concentration. Results Case mothers less often had an adequate vitamin D status compared with controls (27% vs. 38%; p = 0.002). The use of multivitamin supplements, ethnicity, season and body mass index were associated with vitamin D concentrations. A moderate (odds ratio 1.58, [95%CI 1.08, 2.32]) and deficient (odds ratio 2.15, [95%CI 1.44–3.19]) vitamin D status were associated with CHD in offspring. Conclusion A compromised maternal vitamin D status is associated with an approximately two-fold increased prevalence of CHD in offspring. Therefore, improvement of the periconceptional maternal vitamin D status is recommended.
Keywords: 25 hydroxyvitamin D; apolipoprotein B; cholesterol; high density lipoprotein; high density lipoprotein cholesterol; low density lipoprotein; low density lipoprotein cholesterol; triacylglycerol; vitamin D; adult; aortic coarctation; aortic valve stenosis; article; association; atrioventricular septal defect; birth weight; body mass; case control study; cholesterol blood level; congenital heart malformation; controlled study; ethnicity; Fallot tetralogy; female; gestational age; great vessels transposition; heart ventricle septum defect; human; hypoplastic left heart syndrome; major clinical study; maternal age; maternal blood; pathogenesis; perimembranous ventricular septal defect; pulmonary valve stenosis; questionnaire; smoking; triacylglycerol blood level

Ventricular assist device in a failing total cavopulmonary connection: A new step-by-step approach - Napoleone, C.P.; Cascarano, M.T.; Deorsola, L.; Valori, A. (Interactive Cardiovascular and Thoracic Surgery, 2018)
The management of failing Fontan patients with mechanical circulatory support has been reported with unsatisfactory results. A 5-yearold girl, listed for heart transplantation for failing Fontan, underwent rescue extracorporeal membrane oxygenation support. As it was necessary to move the patient to the Berlin Heart Excor, a step-by-step approach was designed to obtain a gradual adaptation to this form of support. A central extracorporeal membrane oxygenation, with a Berlin Heart apical and aortic cannulae, was implanted leaving the previously positioned femoral vein cannula in parallel with the outflow apical one. The femoral vein cannula was removed when the lungs recovered from the effects of surgical trauma. Four days later, the Fontan fenestration was closed, and after 4 more days, a gradual reduction of gas support was planned without problems. Oxygenator was then removed, and 4 days later, a 30-ml Berlin Heart EXCOR ventricle replaced the centrifugal pump. This sequential approach, which has never been described before, can improve the results of the ventricular assist device support in failing Fontan patients, because it allows a gradual adaptation, even in patients with damaged lungs.
Keywords: cannula; centrifugal pump; oxygenator; Quadrox; ventricular assist device; article; case report; cavopulmonary connection; child; clinical article; extracorporeal oxygenation; female; femoral vein; Fontan procedure; heart hemodynamics; heart transplantation; human; lung; lung injury; preschool child; priority journal; surgical technique; treatment failure; treatment indication; EXCOR; Quadrox

Histopathological abnormalities in the central arteries and veins of Fontan subjects - Hays, B.S.; Baker, M.; Laib, A.; Tan, W.; Udholm, S.; Goldstein, B.H.; Sanders, S.P.; Opotowsky, A.R.; Veldtman, G.R. (Heart, 2018)
Objective Fontan circulations have obligatory venous hypertension, depressed cardiac output and abnormal arterial elastance. Ventriculovascular coupling is known to be abnormal, but the underlying mechanisms are poorly defined. We aim to describe the histopathological features of vascular remodelling encountered in the central arteries and veins in the Fontan circulation as a possible underlying pathological representation of abnormal ventriculovascular coupling. Methods Postmortemvasculature (inferior vena cava (IVC), superior vena cava (SVC), pulmonary artery (PA), pulmonary vein (PV) and aorta) of 13 patients with a Fontan circulation (mean age 29.9 years, range 9.0-59.8 years) and 2 biventricular controls (ages 17.9 and 30.2 years) was examined. Results IVC and SVC: Eccentric and variable intimal fibromuscular proliferation occurred in 11 Fontan subjects. There was variable loss of medial smooth muscle bundles with reciprocal replacement with dense collagenous tissue. PA: Similar intimal fibromuscular proliferation was seen; however, these intimal changes were accompanied by medial thinning rather than expansion, medial myxoid degeneration and elastic alteration. PV: The PVs demonstrated intimal fibroproliferation and disorganisation of the muscular media. Aorta: The aortic lamina intima was thickened, with associated fibromuscular proliferation and elasticisation. There was also moderate lymphocytic inflammation in the aortic wall. Conclusions Vascular architectural remodelling is common in Fontan patients. The central veins demonstrate profound changes of eccentric intimal expansion and smooth muscle replacement with collagen. The pulmonary demonstrated abnormal intimal proliferation, and aortic remodelling was characterised by intima lamina thickening and a moderate degree of aortic wall inflammation.
Keywords: adult; article; child; circulation; clinical article; controlled study; descending aorta; double inlet left ventricle; female; great vessels transposition; heart right ventricle double outlet; histopathology; human; human cell; human tissue; hypoplastic left heart syndrome; immunohistochemistry; inferior cava vein; male; morphometry; priority journal; pulmonary artery; pulmonary vein; superior cava vein; tricuspid valve atresia

The onset of asymptomatic amiodarone-induced thyrotoxicosis in an adolescent male - Milyani, A.A.; Al-Agha, A.E. (Current Pediatric Research, 2018)
The use of amiodarone is associated with many organ-specific side effects, of which thyroid gland dysfunction constitute up to 35% of them. Amiodarone-induced thyrotoxicosis can occur in either of two forms, type 1 or type 2, depending on whether there was a positive history of thyroid dysfunction prior to the use of amiodarone therapy or not, respectively. A unique underlying pathophysiology discerns one type from another, which is why early differentiation is pivotal to the rapid institution of appropriate therapy that is contingent on an accurate and correct diagnosis. We report a case of a 15-year-old adolescent with type 2 amiodarone-induced thyrotoxicosis, a rare presentation of thyrotoxicosis in children.
Keywords: septostomy balloon catheter; amiodarone; antinuclear antibody; double stranded DNA antibody; parietal cell antibody; prednisone; smooth muscle antibody; steroid; thyroglobulin antibody; thyroid peroxidase antibody; adolescent; article; case report; clinical article; color Doppler flowmetry; congenital heart disease; drug dose reduction; drug induced disease; euthyroidism; follow up; Fontan procedure; free liothyronine index; free thyroxine index; hemodynamics; human; hyperactivity; male; paroxysmal tachycardia; pathophysiology; steroid therapy; supraventricular tachycardia; thorax pain; thyroid crisis; thyroid disease; thyroid function test; thyrotoxicosis; thyrotropin blood level

The major clinical presentations and echocardiographic features of structural cardiac disease among children in Kordofan, Sudan - Mustafa, A.E.M.; Tahir Ali, N.M.; Elrahim, S.Y.A.; Bharti, R.K.R.; Chaudhary, S. (Pakistan Journal of Medical and Health Sciences, 2018)
Background: Patterns of heart diseases differ between the high income countries and low income countries.1, 2 Acquired heart diseases like RHD, cardiomyopathies, pericarditis are still a public health burden while congenital heart diseases still carry a poor outcome among children3. The absence of early diagnosis, surgical intervention and inadequate access to medication and the existing burden of communicable diseases increases the strain on a staggering economy of most sub Saharan countries. Aim: To assess the clinical and echocardiographic pattern of cardiac disease in children in Kordofan state and to develop a road map plan of their further management. Methods: An analytical cross sectional hospital based study. The study included the children of age groups 1 day up to 18 years with diagnosed or strongly suspected congenital or acquired cardiac disease who have their follow up in the pediatric sections of El-Obied hospitals in the western central part of the Sudan. Every child in the study group was assessed clinically with focused history taken and relevant physical examination. Chest x-ray and proper echocardiography was done for every child in the study group. Management plan was put by the pediatric cardiologist for all the children in the study group. Eighty children were enrolled in this study. Results: 80 children studied, 55% were males and females represent 45%. Most of the children with cardiac disease in the study were from the age group 1-5 years (27.5%) followed by infants (26.2%).after that, 5-10 years, more than 10 years and less than one month. Nine patients (11.25%) were severely affected, 26 (32.5%) were moderately affected and the growth of 45 (56.25%) was normal. Clinical evaluation of the study group revealed that, 19 children (24%) presented with respiratory symptoms and /or respiratory distress. A cardiac murmur was heard in most of the patients in this series, systolic murmurs heard in 55 patients (69%) of which 21 were pansystolic (26%) and 8 were ejection systolic murmurs (10%). Hepatomegaly was found in 25 patients (31%) and Hepatosplenomegaly in 4 patients (5%). Down syndrome was found in 5 patients (6%), William syndrome in one patient. Congenital HD found in 56 patients (70%) and acquired HD in 24 (30%), 19 patients (79% of the acquired heart disease and 23.7% of the total study group was diagnosed as having rheumatic heart disease and cardiomyopathy was found in 5 patients (20.8% of acquired heart disease). Conclusion: Rheumatic cardiac disease is preventable through the proper and complete antibiotic treatment of streptococcal pharyngitis and tonsillitis and it is vital to apply and strict to the recommendations of the national program of prevention of rheumatic fever and rheumatic heart disease.
Keywords: arterial trunk; article; bacterial endocarditis; cardiologist; cardiomegaly; cardiomyopathy; child; clinical feature; dextrocardia; echocardiography; Fallot tetralogy; female; follow up; heart disease; heart left right shunt; heart murmur; heart single ventricle; hepatomegaly; hepatosplenomegaly; human; infant; major clinical study; male; newborn; physical examination; pulmonary valve atresia; pulmonary valve stenosis; respiratory distress; rheumatic fever; rheumatic heart disease; Sudan; systolic heart murmur; thorax radiography; tricuspid valve atresia

Chromosomal Abnormalities Affect the Surgical Outcome in Infants with Hypoplastic Left Heart Syndrome: A Large Cohort Analysis - Zakaria, D.; Tang, X.; Bhakta, R.; ElHassan, N.O.; Prodhan, P. (Pediatric Cardiology, 2018)
Patients with hypoplastic left heart syndrome (HLHS) can have associated genetic abnormalities. This study evaluated the incidence of genetic abnormalities among infants with HLHS and the short-term outcomes of this population during the first hospitalization. This is a retrospective analysis of the multi-center Pediatric Heath Information System database of infants with HLHS who underwent Stage I Norwood, Hybrid, or heart transplant during their first hospitalization from 2004 through 2013. We compared clinical data between infants with and without genetic abnormality, among the three most common chromosomal abnormalities, and between survivors and non-survivors. Multivariable analysis was completed to evaluate predictors of mortality among patients with genetic abnormalities. A total of 5721 infants with HLHS were identified; 282 (5%) had associated genetic abnormalities. The three most common chromosomal abnormalities were Turner (25%), DiGeorge (22%), and Downs (12.7%) syndromes. Over the study period, the number of patients with genetic abnormalities undergoing cardiac operations increased without any significant increases in mortality. Infants with genetic abnormalities compared to those without abnormalities had longer hospital length of stay and higher morbidity and mortality. Variables associated with mortality were lower gestational age, longer duration of vasopressor therapy, need for dialysis, and cardiopulmonary resuscitation; and complicated clinical course as suggested by necrotizing enterocolitis, septicemia. Presence of any genetic abnormality in infants with HLHS undergoing cardiac surgery is associated with increased mortality and morbidity. Timely genetic testing, appropriate family counseling, and thorough preoperative case selection are suggested for these patients for any operative intervention.
Keywords: article; chromosome aberration; cohort analysis; dialysis; DiGeorge syndrome; disease association; disease course; Down syndrome; family counseling; female; genetic screening; gestational age; heart graft; heart surgery; human; hypoplastic left heart syndrome; infant; infant mortality; length of stay; major clinical study; male; morbidity; necrotizing enterocolitis; Norwood procedure; resuscitation; retrospective study; septicemia; short term survival; survival prediction; survivor; treatment duration; treatment outcome; Turner syndrome

Second annual Pediatric Interagency Registry for Mechanical Circulatory Support (Pedimacs) report: Pre-implant characteristics and outcomes - Blume, E.D.; VanderPluym, C.; Lorts, A.; Baldwin, J.T.; Rossano, J.W.; Morales, D.L.S.; Cantor, R.S.; Miller, M.A.; St. Louis, J.D.; Koehl, D.; Sutcliffe, D.L.; Eghtesady, P.; et al. (Journal of Heart and Lung Transplantation, 2018)
Background Expanded use of pediatric ventricular assist devices (VADs) has decreased mortality in children awaiting heart transplantation. Pediatric Interagency Registry for Mechanical Circulatory Support (Pedimacs), a National Heart, Lung, and Blood Institute–sponsored North American database, provides a platform to understand this emerging population. Methods Between September 2012 and September 2016, patients aged younger than 19 years who underwent VAD implantation were enrolled in Pedimacs. FDA approved durable devices as well as temporary support devices were included. The second annual report updates the current Pedimacs data. Patients implanted with temporary devices are included in Pedimacs and this analysis includes this group of paracorporeal continuous flow VADs. Results Over the 4 years, 42 hospitals implanted 432 devices in 364 patients less than 19 yrs of age. Diagnoses included cardiomyopathy in 223 (61%), myocarditis in 41 (11%), and congenital heart disease in 77 (21%), of which 48 had single-ventricle physiology. At implant, 87% were at Intermacs patient profile 1 or 2. The age distribution of children (59% male) supported on VAD included 69 (19%) aged younger than 1 year, 66 (18%) aged 1 to 6 years, 56 (15%) aged 6 to 10 years, and 173 (48%) aged 11 to 19 years. Median follow-up was 2.2 months (range, 1 day to 41.5 months). Median (interquartile) age at implant was 1.7 (0.3–10.0) years for paracorporeal continuous-flow pumps (n = 60), 1.7 (0.4–5.3) years for paracorporeal pulsatile pumps (n = 105), and 15.0 (11.3–16.9) years for implantable continuous-flow pumps (n = 174). Support strategies included LVAD in 293 (80%), biventricular device in 55 (15%), and total artificial heart in 8 (2%). Nearly 50% of patients underwent transplantation within 6 months, with overall mortality of 19%. Adverse event burden continues to be high. Conclusions Pedimacs constitutes the largest longitudinal pediatric VAD registry. Preimplant data across centers will be helpful at creating shared protocols with which to improve outcomes. Adverse events continue to be the major challenge, especially among the young critically ill children with complex congenital disease.
Keywords: biventricular assist device; left ventricular assist device; adolescent; adult; article; assisted circulation; cardiomyopathy; cause of death; child; congenital heart disease; controlled study; female; follow up; heart transplantation; human; infant; longitudinal study; male; mechanical circulatory support; mortality; myocarditis; preschool child; priority journal; quality of life; school child; young adult

Stress and quality of life among parents of children with congenital heart disease referred for psychological services - Kaugars, A.; Shields, C.; Brosig, C. (Congenital Heart Disease, 2018)
Objective: The study examined parent stress and health-related quality of life (HRQOL) among families of children with congenital heart disease (CHD) referred for psychological services. Methods: Parents of 54 children (85% boys) aged 3 to 13 (Mage = 7.48, SD = 2.38) completed measures to assess parenting stress (Parenting Stress Index – Short Form; Pediatric Inventory for Parents) and the PedsQL Family Impact Module. Medical information was retrieved from medical record review. Results: Half of parents of children with single ventricle anatomy had clinically significant levels of parenting stress. Parents of children with single ventricle anatomy reported more frequent illness-related stress and more difficulty dealing with illness-related stress than parents of children with two ventricle anatomy. Younger gestational age at birth and referral for attention or behavior problems were associated with greater likelihood of parent at-risk psychosocial functioning. Conclusions: Among children referred for psychological services, many parents report significant stress and significant negative impact of the child's medical condition on the family. Results underscore the need to consider assessing parent psychosocial functioning and providing additional support for parents of children with CHD.
Keywords: adolescent; article; attention deficit disorder; behavior disorder; child; congenital heart disease; controlled study; female; gestational age; heart single ventricle; human; infant; major clinical study; male; mental health service; parental stress; patient referral; pediatrics; priority journal; quality of life; retrospective study; social psychology

Children with hypoplastic left heart syndrome have lower quality of life than healthy controls and children with other illnesses - Dempster, N.; Cua, C.L.; Wernovsky, G.; Caris, E.; Neely, T.; Allen, R.; Butz, C. (Cardiology in the Young, 2018)
Objective Previous studies suggest that children with congenital cardiac diagnoses report lower quality of life when compared with healthy norms. A few studies have evaluated quality of life specifically in children born with hypoplastic left heart syndrome, a condition requiring several surgeries before age three. The aim of this study was to use an empirically validated and standardised measure - the Pediatric Quality of Life Inventory - to evaluate quality of life in children with hypoplastic left heart syndrome and compare the findings with similar, medically complicated samples. Methods The parent-report Pediatric Quality of Life Inventory was administered, and demographic information was collected through an internet portal. A total of 121 caregivers of children with hypoplastic left heart syndrome responded. The sample included children aged 2-18 years (M=10.81 years). Independent sample t-tests were used to compare our sample with published norms of healthy children and children with acute or chronic illnesses. Results Children with hypoplastic left heart syndrome were rated as having significantly lower overall quality-of-life scores (M=59.69) compared with published norms of children without medical diagnoses (M=83.00) and those with acute (M=78.70) or chronic (M=77.19) illnesses (p<0.001). Children with hypoplastic left heart syndrome complicated by a stroke or seizure (15%) reported the lowest quality of life. The results held for all subscales (p<0.001). Conclusions Children with hypoplastic left heart syndrome appear to be a significantly vulnerable population with difficulties in functioning across psychosocial domains and across the age span. Further research is required to facilitate early identification of the need for resources for these children and families, especially for children who experience additional medical complications.
Keywords: acute disease; adolescent; adult; article; caregiver; cerebrovascular accident; child; chronic disease; controlled study; demography; female; functional status; human; hypoplastic left heart syndrome; Internet; male; Pediatric Quality of Life Inventory; quality of life; seizure

Utilisation of early intervention services in young children with hypoplastic left heart syndrome - Mussatto, K.A.; Hollenbeck-Pringle, D.; Trachtenberg, F.; Sood, E.; Sananes, R.; Pike, N.A.; Lambert, L.M.; Mahle, W.T.; Goldberg, D.J.; Goldberg, C.S.; Dunbar-Masterson, C.; Otto, M.; et al. (Cardiology in the Young, 2018)
Objective Children with hypoplastic left heart syndrome are at a risk for neurodevelopmental delays. Current guidelines recommend systematic evaluation and management of neurodevelopmental outcomes with referral for early intervention services. The Single Ventricle Reconstruction Trial represents the largest cohort of children with hypoplastic left heart syndrome ever assembled. Data on life events and resource utilisation have been collected annually. We sought to determine the type and prevalence of early intervention services used from age 1 to 4 years and factors associated with utilisation of services. Methods Data from 14-month neurodevelopmental assessment and annual medical history forms were used. We assessed the impact of social risk and geographic differences. Fisher exact tests and logistic regression were used to evaluate associations. Results Annual medical history forms were available for 302 of 314 children. Greater than half of the children (52-69%) were not receiving services at any age assessed, whereas 20-32% were receiving two or more therapies each year. Utilisation was significantly lower in year 4 (31%) compared with years 1-3 (with a range from 40 to 48%) (p<0.001). Social risk factors were not associated with the use of services at any age but there were significant geographic differences. Significant delay was reported by parents in 18-43% of children at ages 3 and 4. Conclusion Despite significant neurodevelopmental delays, early intervention service utilisation was low in this cohort. As survival has improved for children with hypoplastic left heart syndrome, attention must shift to strategies to optimise developmental outcomes, including enrolment in early intervention when merited.
Keywords: article; biogeographic region; brain development; child; cognitive therapy; cohort analysis; developmental delay; early childhood intervention; follow up; health care utilization; human; hypoplastic left heart syndrome; medical history; mental disease; occupational therapy; physiotherapy; speech therapy; survival rate

Neurodevelopmental Outcome in Children with Single Ventricle after Total Cavopulmonary Connection - Vahsen, N.; Bröder, A.; Hraska, V.; Schneider, M. (Klinische Padiatrie, 2018)
Background The purpose of the present study was to assess a broad range of neuropsychological outcome variables in children with functionally single ventricle hearts after a total cavopulmonary connection and to examine potential risk factors for impaired neurodevelopment. Patients & Method A total of 104 patients aged 2 to 20 years underwent follow-up standardized psychological testing, including measures of intelligence, motor function, visuospatial abilities, behavioural outcome and health-related quality of life. Results With a mean fluid intelligence score of 93.0 and a mean crystallized intelligence score of 92.3, patients scored significantly lower on tests of intelligence compared to the general population (p<0.001). Reduced motor function was found in 34% of the patients (p<0.001), impaired visuospatial abilities in 51%; parents reported significantly more behavioural problems (p<0.001). There was no difference in the self-reported quality of life compared to the general population. Risk factors for reduced fluid intelligence were deep hypothermic circulatory arrest times (p=0.03) and complications causing suboptimal brain perfusion prior to the total cavopulmonary connection (e. g. seizures; p=0.04). Conclusions Patients with functionally single ventricle hearts palliated with a total cavopulmonary connection are at an increased risk of neurodevelopmental delays and behavioural disorders. Nevertheless, they adapt well in terms of quality of life. Early diagnostics and interventions are necessary when developmental delays are suspected.
Keywords: adolescent; adult; article; behavior; brain perfusion; cavopulmonary connection; child; deep hypothermic circulatory arrest; depth perception; developmental delay; early diagnosis; early intervention; female; follow up; heart single ventricle; human; intelligence; major clinical study; male; mental development; motor performance; nervous system development; neuropsychological test; quality of life; risk factor

The congenital heart disease genetic network study: Cohort description - Hoang, T.T.; Goldmuntz, E.; Roberts, A.E.; Chung, W.K.; Kline, J.K.; Deanfield, J.E.; Giardini, A.; Aleman, A.; Gelb, B.D.; Neal, M.M.; Porter, G.A.; Kim, R.; et al. (PLoS ONE, 2018)
The Pediatric Cardiac Genomics Consortium (PCGC) designed the Congenital Heart Disease Genetic Network Study to provide phenotype and genotype data for a large congenital heart defects (CHDs) cohort. This article describes the PCGC cohort, overall and by major types of CHDs (e.g., conotruncal defects) and subtypes of conotrucal heart defects (e.g., tetralogy of Fallot) and left ventricular outflow tract obstructions (e.g., hypoplastic left heart syndrome). Cases with CHDs were recruited through ten sites, 2010–2014. Information on cases (N = 9,727) and their parents was collected through interviews and medical record abstraction. Four case characteristics, eleven parental characteristics, and thirteen parent-reported neurodevelopment outcomes were summarized using counts and frequencies and compared across CHD types and subtypes. Eleven percent of cases had a genetic diagnosis. Among cases without a genetic diagnosis, the majority had conotruncal heart defects (40%) or left ventricular outflow tract obstruction (21%). Across CHD types, there were significant differences (p<0.05) in the distribution of all four case characteristics (e.g., sex), four parental characteristics (e.g., maternal pregestational diabetes), and five neurodevelopmental outcomes (e.g., learning disabilities). Several characteristics (e.g., sex) were also significantly different across CHD subtypes. The PCGC cohort is one of the largest CHD cohorts available for the study of genetic determinants of risk and outcomes. The majority of cases do not have a genetic diagnosis. This description of the PCGC cohort, including differences across CHD types and subtypes, provides a reference work for investigators who are interested in collaborating with or using publically available resources from the PCGC.
Keywords: article; child; cohort analysis; congenital heart disease; congenital heart malformation; female; genetic disorder; genetics; heart left ventricle outflow tract obstruction; human; infant; learning disorder; major clinical study; male; maternal diabetes mellitus; mental disease

Current surgical outcomes of congenital heart surgery for patients with down syndrome in Japan - Hoashi, T.; Hirahara, N.; Murakami, A.; Hirata, Y.; Ichikawa, H.; Kobayashi, J.; Takamoto, S. (Circulation Journal, 2018)
Background: Current surgical outcomes of congenital heart surgery for patients with Down syndrome are unclear. Methods and Results: Of 29,087 operations between 2008 and 2012 registered in the Japan Congenital Cardiovascular Surgery Database (JCCVSD), 2,651 were carried out for patients with Down syndrome (9%). Of those, 5 major biventricular repair procedures [ventricular septal defect repair (n=752), atrioventricular septal defect repair (n=452), patent ductus arteriosus closure (n=184), atrial septal defect repair (n=167), tetralogy of Fallot (TOF) repair (n=108)], as well as 2 major single ventricular palliations [bidirectional Glenn (n=21) and Fontan operation (n=25)] were selected and their outcomes were compared. The 90-day and in-hospital mortality rates for all 5 major biventricular repair procedures and bidirectional Glenn were similarly low in patients with Down syndrome compared with patients without Down syndrome. On the other hand, mortality after Fontan operation in patients with Down syndrome was significantly higher than in patients without Down syndrome (42/1,558=2.7% vs. 3/25=12.0%, P=0.005). Conclusions: Although intensive management of pulmonary hypertension is essential, analysis of the JCCVSD revealed favorable early prognostic outcomes after 5 major biventricular procedures and bidirectional Glenn in patients with Down syndrome. Indication of the Fontan operation for patients with Down syndrome should be carefully decided.
Keywords: article; artificial ventilation; atrioventricular septal defect; catheterization; child; Down syndrome; Fallot tetralogy; female; heart atrium septum defect; heart surgery; heart ventricle septum defect; home oxygen therapy; hospital discharge; hospital mortality; hospital readmission; human; length of stay; lung vascular resistance; major clinical study; male; multicenter study; outcome assessment; patent ductus arteriosus; pH; postoperative period; pulmonary hypertension; retrospective study; surgical mortality

Exercise performance after univentricular palliation - Talwar, S.; Kumar, M.; Sreenivas, V.; Gupta, V.; Choudhary, S.; Airan, B. (Annals of Pediatric Cardiology, 2018)
Background : The optimal timing, need for primary/staged procedure in patients undergoing univentricular palliation, is debatable. Aims : We performed this study to assess the exercise performance of patients undergoing various forms of univentricular palliation. Setting and Design : This was a retrospective, prospective comparative study conducted at a multispecialty tertiary referral center. Patients and Methods : Between January 2012 and June 2015, 117 patients undergoing either bidirectional Glenn (BDG) (n = 43) or Fontan (total cavopulmonary connection [TCPC]) (n = 74) underwent exercise testing. Statistical Analysis : Comparisons between subgroups for continuous data were made with Student's ttest if normally distributed and Wilcoxon ranksum test otherwise. Tests between subgroups for qualitative data were made with Pearson's Chisquare test. Results : Patients who underwent BDG with open antegrade pulmonary blood flow (APBF) had higher saturations (oxygen saturation [SpO2]) compared to those without it (87.5 ± 5.0% vs. 81.1 ± 4.8%; P = 0.0001). However, we found no differences in exercise parameters of patients undergoing BDG with or without APBF. Extracardiac TCPC (n = 42) patients demonstrated better exercise capacity (15.0 ± 7.7 vs. 11.2 ± 6.2 min; P = 0.02) and increased SpO2 on exercise (87.0 ± 8.0% vs. 83.4 ± 7.6%; P ≤ 0.05) compared to lateral tunnel TCPC (n = 32). Fenestrated TCPC (n = 30) patients had higher exercise capacity reflected by higher metabolic equivalents (METs) consumption (6.4 ± 2.3 vs. 5.2 ± 2.0 METs, P = 0.02), fewer pleural effusions (7.0 ± 3.2 vs. 9.2 ± 6.2 days, P ≤ 0.05), and lower hospital stay (9.5 ± 4.0 vs. 12.7 ± 7.7 days, P = 0.04) compared to nonfenestrated TCPC (n = 44) patients. Conclusions : We observed no differences in exercise parameters of patients undergoing BDG with or without APBF. Extracardiac TCPC patients had better exercise capacity but longer postoperative hospital stay and pleural effusions than patients with lateral tunnel Fontan. Fenestrated TCPC patients seemed to fare better than nonfenestrated ones. Patients undergoing TCPC had better exercise capacity than patients undergoing BDG alone.
Keywords: anxiety; article; cavopulmonary connection; child; chronotropism; cohort analysis; comparative study; electrocardiography; exercise; female; Fontan procedure; heart rate; heart single ventricle; hospitalization; human; lung blood flow; major clinical study; male; metabolic equivalent; outpatient department; oxygen saturation; pleura effusion; prospective study; retrospective study; tertiary care center

First Polish analysis of the treatment of advanced heart failure in children with the use of BerlinHeart EXCOR® mechanical circulatory support - Pawlak, S.; Przybylski, R.; Skalski, J.; Śliwka, J.; Kansy, A.; Grzybowski, A.; Wierzyk, A.; Białkowski, J.; Maruszewski, B.; Zembala, M. (Kardiologia Polska, 2018)
Background: The treatment of advanced heart failure (HF) in children and infants poses a serious management problem. Heart failure in that patient group is usually of congenital aetiology. The treatment schedules for paediatric patients are in most cases adapted from the guidelines for treatment of adults. Up to 2009, the treatment of that extremely difficult group of patients was limited to pharmacological therapy and occasional heart transplantations. Constantly increasing problems with recruiting donors, especially for the paediatric group, contribute to the fact that mechanical support with the use of ventricular assist devices is for many children the only chance of surviving the period of waiting for a heart donor. Aim: The aim of the study was to analyse the outcomes of circulatory support in Poland and to assess the advisability of this method for treatment of children with severe HF. Methods: This treatment of paediatric patients is currently used in three Polish centres. From December 28, 2009 to August 1, 2015, 27 implantations of BerlinHeart EXCOR® mechanical circulatory support system were performed in children aged from one month to 16 years (10 patients below one year of age; 37%). Left ventricular assist devices were implanted to 21 patients, whereas the remaining children received biventricular support. The most common reason for using this method was HF developed in the course of cardiomyopathy. In one case, HF after Fontan operation was the indication. Results: The duration of the circulatory support period ranged from six to 1215 days. It was followed by successful heart transplantations in 10 (37%) patients, in five (18.1%) it resulted in regeneration of the heart, enabling explantation of the device, whereas three children are still waiting for transplantations. Nine (33%) children died during the therapy because of thromboembolic complications. Conclusions: As follows from our data, circulatory support utilising the BerlinHeart EXCOR® system is an effective and promising method used as a bridge to cardiac transplantation, or for regeneration of the myocardium in paediatric patients. In the group of the youngest and the most difficult patients, the method requires close cooperation of the medical and nursing personnel.
Keywords: BerlinHeart EXCOR; biventricular assist device; heart assist device; left ventricular assist device; LEVITRONIX; ventricular assist device; acetylsalicylic acid; alteplase; antivitamin K; dipyridamole; heparin; inotropic agent; low molecular weight heparin; prostacyclin; activated partial thromboplastin time; adolescent; article; cardiomyopathy; cardiopulmonary insufficiency; child; childhood mortality; clinical article; clinical effectiveness; cooperation; device removal; device therapy; disease severity; enteric feeding; extracorporeal oxygenation; female; Fontan procedure; heart failure; heart transplantation; human; infant; international normalized ratio; lung embolism; male; medical staff; nursing staff; Poland; Polish citizen; retrospective study; rotary pump support; survival rate; thromboembolism; thrombosis; treatment duration; treatment indication; BerlinHeart EXCOR; LEVITRONIX

Externally applied compression therapy for Fontan patients - Hernandez, J.; Chopski, S.G.; Lee, S.; Moskowitz, W.B.; Throckmorton, A.L. (Translational Pediatrics, 2018)
Background: Limited therapeutic options are available for Fontan patients with dysfunctional or failing single ventricle physiology. This study describes the evaluation of an alternative, non-invasive, at-home therapeutic compression treatment for Fontan patients. Our hypothesis is that routinely administered, externally applied compression treatments to the lower extremities will augment systemic venous return, improve ventricular preload, and thus enhance cardiac output in Fontan patients. Methods: To initially evaluate this hypothesis, we employed the NormaTec pneumatic compression device (PCD) in a pilot clinical study (n=2). This device is composed of inflatable trouser compartments that facilitate circumferentially and uniformly applied pressure to a patient’s lower extremities. Following an initial health screening, test subjects were pre-evaluated with a modified-Bruce treadmill exercise stress test, and baseline data on cardiorespiratory health was collected. After training, test subjects conducted 6 days of external compression therapy at-home. Subjects were then re-evaluated with a final treadmill stress test and data acquisition of new cardiorespiratory parameters. Results: Both subjects demonstrated improvement in exercise duration time, peak oxygen volume, and ventilator threshold, as compared to the baseline evaluation. Conclusions: These findings are promising and provide the foundation for future studies that will focus on increasing study participation (sample size) to better assess the clinical benefit of compression therapy for Fontan patients.
Keywords: intermittent pneumatic compression device; NormaTec; adolescent; adult; aerobic capacity; article; cardiorespiratory fitness; cardiorespiratory parameters; cardiovascular parameters; clinical article; clinical evaluation; clinical study; compression therapy; controlled study; exercise; exercise duration time; exercise intensity; externally applied compression therapy; female; Fontan procedure; heart function; home care; human; inflatable trouser compartment; information processing; lower limb; male; oxygen consumption; oxygen uptake efficiency slope; peak oxygen volume; peak respiratory exchange rate; pilot study; pressure; reevaluation; respiratory tract parameters; training; treadmill exercise; treatment outcome; ventilator threshold; ventilatory threshold; NormaTec

Brown fat necrosis with calcifications in the newborn: Risk factors, radiographic findings, and clinical course - Golden, E.; Dickson, P.; Simoneaux, S. (Indian Journal of Radiology and Imaging, 2018)
Objective: To describe the radiographic appearance of subclinical calcified brown fat necrosis and the associated clinical and laboratory findings. Materials and Methods: Picture Archiving and Communications Sytem (PACS) was searched using keywords 'soft tissue calcification' and 'chest.' The clinical record was searched for prior cardiac surgery, bypass, Extracorporeal Membrane Oxygentation (ECMO) and prostaglandin use. Age when calcifications were first detected, location, resolution, and associated laboratory abnormalities were recorded. Results: Nine patients were identified. None had skin lesions. All patients had congenital heart disease and had experienced cardiac/respiratory arrest and/or severe hypotension 1-6 weeks before soft tissue calcifications occurred. Calcifications resolved by 9 weeks to 5 months in 3 patients. The remaining were either deceased or lacked follow-up imaging. Renal ultrasound was performed in all but 1 patient. Nephrocalcinosis was only seen in 1 patient. Conclusion: Brown fat necrosis is subclinical, diagnosed on plain film, and likely self-limited. It occurs in term and preterm infants who have undergone significant systemic stress and carries a poor prognosis.
Keywords: prostaglandin; article; atrioventricular canal; bicuspid aortic valve; brown adipose tissue; bypass surgery; clinical article; clinical feature; congenital heart disease; disease course; drug use; extracorporeal oxygenation; fat necrosis; female; follow up; heart failure; heart right ventricle double outlet; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; hypotension; induced hypothermia; infant; kidney calcification; male; neuroimaging; newborn; newborn disease; patent ductus arteriosus; patient identification; pediatric radiologist; picture archiving and communication system; prematurity; renography; respiratory arrest; respiratory failure; risk factor; skin defect; soft tissue calcification; tricuspid valve atresia; trisomy 18

Recent advances and challenges on application of tissue engineering for treatment of congenital heart disease - Mantakaki, A.; Fakoya, A.O.J.; Sharifpanah, F. (PeerJ, 2018)
Congenital heart disease (CHD) affects a considerable number of children and adults worldwide. This implicates not only developmental disorders, high mortality, and reduced quality of life but also, high costs for the healthcare systems. CHD refers to a variety of heart and vascular malformations which could be very challenging to reconstruct the malformed region surgically, especially when the patient is an infant or a child. Advanced technology and research have offered a better mechanistic insight on the impact of CHD in the heart and vascular system of infants, children, and adults and identified potential therapeutic solutions. Many artificial materials and devices have been used for cardiovascular surgery. Surgeons and the medical industry created and evolved the ball valves to the carbon-based leaflet valves and introduced bioprosthesis as an alternative. However, with research further progressing, contracting tissue has been developed in laboratories and tissue engineering (TE) could represent a revolutionary answer for CHD surgery. Development of engineered tissue for cardiac and aortic reconstruction for developing bodies of infants and children can be very challenging. Nevertheless, using acellular scaffolds, allograft, xenografts, and autografts is already very common. Seeding of cells on surface and within scaffold is a key challenging factor for use of the above. The use of different types of stem cells has been investigated and proven to be suitable for tissue engineering. They are the most promising source of cells for heart reconstruction in a developing body, even for adults. Some stem cell types are more effective than others, with some disadvantages which may be eliminated in the future.
Keywords: tissue scaffold; biomaterial; aortic coarctation; article; bone marrow cell line; cardiac scaffold; cardiac stem cell; congenital heart disease; Ebstein anomaly; embryonic stem cell; extracellular matrix; health care system; heart atrium septum defect; heart ventricle septum defect; human; hypoplastic left heart syndrome; induced pluripotent stem cell; lung vein drainage anomaly; nonhuman; patent ductus arteriosus; pulmonary valve atresia; pulmonary valve stenosis; stem cell transplantation; survival rate; tissue engineering; tricuspid valve atresia

Nurse-driven analgesia and sedation in pediatric patients with univentricular hearts requiring extracorporeal life support after first-stage palliation surgery: A pilot study - Michel, J.; Hofbeck, M.; Gerbig, I.; Icheva, V.; Heimberg, E.; Jost, W.; Schlensak, C.; Kumpf, M.; Blumenstock, G.; Neunhoeffer, F. (Paediatric Anaesthesia, 2017)
Background: Few data are available regarding requirements of sedation and analgesia in children during extracorporeal life support. Aims: The aim of this study was to evaluate if children with functionally univentricular hearts on extracorporeal life support after first-stage palliation surgery have higher requirement of analgesics and sedatives compared with children without extracorporeal life support using a goal-directed nurse-driven analgesia and sedation protocol. Methods: This prospective observational matched case-control pilot study was conducted at a cardiac pediatric intensive care unit of a tertiary referral center. Seventeen patients with functionally univentricular hearts including hypoplastic left heart syndrome who were on extracorporeal life support after first-stage palliation surgery were enrolled from July 2012 to January 2017. Seventeen matched patients served as controls. Doses of morphine, midazolam, clonidine, and muscle relaxants as well as sedation scores (COMFORT behavior scale and the nurse interpretation of sedation scale) were assessed according to a nurse-driven protocol every 8 hours up to 120 hours after first-stage palliation surgery. Results: Sedation scores were equal in the extracorporeal life support group and in the control group at most points in time. There was no significant difference in cumulative doses of morphine and midazolam. However, children of the extracorporeal life support group received higher doses of midazolam and morphine at some points in time. Conclusion: A nurse-driven protocol for analgesia and sedation of children with extracorporeal life support is feasible. Patients with extracorporeal life support do not need deeper sedation levels and have not higher cumulative sedation requirements than children without extracorporeal life support.
Keywords: blood pump; medos; clonidine; midazolam; morphine; muscle relaxant agent; analgesia; article; case control study; clinical article; controlled study; coronary care unit; extracorporeal oxygenation; female; heart single ventricle; human; infant; male; nurse attitude; observational study; palliative therapy; pediatric intensive care unit; pediatrics; pilot study; priority journal; prospective study; sedation; tertiary care center; deltastream; medos

Health-related quality of life in paediatric patients with congenital heart defects: association with the type of heart defect and the surgical technique - Heusch, A.; Kahl, H.J.; Hensel, K.O.; Calaminus, G. (Quality of Life Research, 2017)
Summary: The aim of the study was to investigate the impact of a number of surgical interventions for a various congenital cardiac defects (CHDs) on self-reported HRQoL. Methods: Patients who had received corrective surgery of several congenital heart defects (surgical VSD closure, Fallot, TGA after atrial or arterial switch or Fontan-type circulation for univentricular AV-connection) were interviewed in the office of their home peadiatric cardiologist. HRQoL in children along 7 dimensions was assessed using a standardised questionnaire (PEDQoL); information on the medical case history of each respondent was also collected. Statistics: HRQoL was assessed in the questionnaire by asking about the frequency (never, rarely, often, always) of specific negative experiences; more frequent experiences indicate a lower quality of life. Frequency expressions were transformed into numerical values (25, 50, 75, 100%), and mean values for HRQoL were calculated for each patient and for each domain. Differences in HRQoL among patients with different types of interventions were analysed using the Mann–Whitney Test or the Kruskal–Wallis Test as appropriate; p values <0.05 were considered to indicate significant differences, while p values <0.1 were considered to indicate notable trends. Results: Patients: 169 patients (60% male, 40% female) were part of the study. The mean age was 11.6 years; 50 patients had surgical VSD closure, 52 surgeries for Tetralogy of Fallot (22 transannular patch, 18 no transannular patch, 12 inaccurate description), 40 had complete transposition of the great arteries (28 atrial switch, 12 arterial switch), 22 had a Fontan-type procedure for univentricular AV-connection. HRQoL differed little among patients with different CHDs for the items “relation to friends,” “interactions in the affected families”, and “own body image”. For other items, notable differences emerged: patients with univentricular hearts rated their physical capacity worse and showed a tendency towards negative ratings in other domains. On the other hand, patients after Fallot or TGA correction tended to rate their HRQoL in several domains as relatively high. Focusing on the mode of surgery for Fallot repair, respectively, TGA correction the only significant difference was found for “physical capacity” in TGA (atrial vs. arterial repair). Mustard patients tended to rate most items worse. Physical capacity was rated worst by patients with a Fontan circulation. Repeated surgery led to lower ratings for all domains except “physical capacity” and “body image”. Conclusions: Different surgical techniques for CHD do not affect children’s and adolescents’ self-reported HRQoL to the extent that one would expect. This observation is in line with observations in groups of children with different chronic diseases. Specialised psychosocial support is necessary in order to maintain this positive self-evaluation and to ensure patients are able to lead autonomous personal and professional lives.
Keywords: arterial switch operation; article; body image; child; clinical assessment; controlled study; Fallot tetralogy; female; great vessels transposition; heart single ventricle; heart ventricle septum defect; human; major clinical study; male; patient-reported outcome; physical capacity; plastic surgery; priority journal; quality of life; school child; social status; surgical technique

Effect of Fontan geometry on exercise haemodynamics and its potential implications - Tang, E.; Wei, Z.; Whitehead, K.K.; Khiabani, R.H.; Restrepo, M.; Mirabella, L.; Bethel, J.; Paridon, S.M.; Marino, B.S.; Fogel, M.A.; Yoganathan, A.P. (Heart, 2017)
Objective Exercise intolerance afflicts Fontan patients with total cavopulmonary connections (TCPCs) causing a reduction in quality of life. Optimising TCPC design is hypothesised to have a beneficial effect on exercise capacity. This study investigates relationships between TCPC geometries and exercise haemodynamics and performance. Methods This study included 47 patients who completed metabolic exercise stress test with cardiac magnetic resonance (CMR). Phase-contrast CMR images were acquired immediately following supine lower limb exercise. Both anatomies and exercise vessel flow rates at ventilatory anaerobic threshold (VAT) were extracted. The vascular modelling toolkits were used to analyse TCPC geometries. Computational simulations were performed to quantify TCPC indexed power loss (iPL) at VAT. Results A highly significant inverse correlation was found between the TCPC diameter index, which factors in the narrowing of TCPC vessels, with iPL at VAT (r=0.723, p<0.001) but positive correlations with exercise performance variables, including minute oxygen consumption (VO 2) at VAT (r=0.373, p=0.01), VO 2 at peak exercise (r=0.485, p=0.001) and work at VAT/weight (r=0.368, p=0.01). iPL at VAT was negatively correlated with VO 2 at VAT (r=0.337, p=0.02), VO 2 at peak exercise (r=0.394, p=0.007) and work at VAT/weight (r=0.208, p=0.17). Conclusions Eliminating vessel narrowing in TCPCs and reducing elevated iPL at VAT could enhance exercise tolerance for patients with TCPCs. These findings could help plan surgical or catheter-based strategies to improve patients' exercise capacity.
Keywords: adolescent; adult; article; blood flow velocity; body weight; cardiovascular magnetic resonance; child; clinical article; controlled study; correlation analysis; exercise; exercise test; exercise tolerance; female; Fontan procedure; hemodynamics; human; lower limb; lung ventilation; male; oxygen consumption; priority journal; school child; simulation; supine position; ventilatory anaerobic threshold

Congenital heart disease and cardiac procedural outcomes in patients with trisomy 21 and Turner syndrome - Morales-Demori, R. (Congenital Heart Disease, 2017)
Congenital heart disease (CHD) is present in approximately 50% of patients with trisomy 21 (T21) and Turner syndrome (TS). According to the American Academy of Pediatrics, every patient with these genetic disorders should have a postnatal echocardiogram. T21 is usually associated with atrioventricular (30%–60%), atrial (16%-21%), or ventricular septal defects (14%–27%). TS is usually associated with left-sided heart disease. However, the spectrum of CHD in these genetic disorders is wider than those mentioned lesions. More cardiac surgical procedures are offered to these patients and that has influenced positively their life expectancy for some CHD conditions. Single ventricular anatomy is associated with high mortality in these genetic disorders (49% in T21 and 83%–91% in TS). The goal of this article is to describe the spectrum of CHD, screening guidelines, and cardiac surgical outcomes in patients with T21 or TS with CHD.
Keywords: antihypertensive agent; beta adrenergic receptor blocking agent; growth hormone; hypocholesterolemic agent; anomalous venous return; aortic arch branching anomaly; aortic coarctation; aortic dilation; aortic dissection; article; atrioventricular septal defect surgery; bicuspid aortic valve; body mass; bronchomalacia; cardiac surgical outcome; cause of death; chylothorax; clinical outcome; congenital heart disease; coronary artery anomaly; diabetes mellitus; disease association; disease severity; electrocardiography; electrophysiology; extracorporeal circulation; follow up; Fontan procedure; heart atrium arrhythmia; heart single ventricle; heart transplantation; hormone substitution; human; hypertension; intellectual impairment; interpersonal communication; language disability; laryngomalacia; lung infection; maternal hypertension; maternal smoking; pacemaker placement; pathogenesis; pathophysiology; physical examination; postoperative complication; practice guideline; pregnancy; prevalence; priority journal; pulmonary hypertension; reoperation; risk factor; scoring system; screening test; sensitivity analysis; sex difference; single ventricular anatomy; sinus node; spectrum; speech disorder; subglottic stenosis; surgical infection; surgical mortality; surgical technique; thorax radiography; tracheomalacia; trisomy 21; Turner syndrome; visuomotor coordination

Psychosocial impact on families with an infant with a hypoplastic left heart syndrome during and after the interstage monitoring period - a prospective mixed-method study - Stoffel, G.; Spirig, R.; Stiasny, B.; Bernet, V.; Dave, H.; Knirsch, W. (Journal of clinical nursing, 2017)
AIMS AND OBJECTIVES: To investigate parents' experiences, coping ability and quality of life while monitoring their sick child with hypoplastic left heart syndrome at home. BACKGROUND: Interstage home monitoring for children with hypoplastic left heart syndrome reduces interstage mortality between Norwood stages I and II. Little is known about the psychosocial impact of interstage home monitoring. DESIGN: Prospective mixed-method study. METHODS: This study assessed the psychosocial impact on parents during interstage home monitoring. This contains for quantitative assessment the Short Form Health Survey questionnaire and the Impact of Family Scale administered one and five weeks following discharge before and after stage II. For qualitative assessment, semi-structured interviews focussing on the postdischarge coping strategies were conducted twice, five weeks after hospital discharge before and after stage II. RESULTS: Ten infants (eight males) with hypoplastic left heart syndrome (n = 7) or other types of univentricular heart malformations (n = 3), and their parents (nine mother/father two-parent households, one single mother) were included. There were no interstage deaths. Mental Health Composite Summary scores were low in both parents (mothers: 40·45 ± 9·07; fathers: 40·58 ± 9·69) and lowest for the item 'vitality' (mothers: 37·0 ± 19·46; fathers: 43·12 ± 25·9) before and after stage II. Impact of Family Scale values showed higher daily and social burdens for mothers. 'Becoming a family' was the most important task as coping strategy to equilibrate the fragile emotional balance. The parents judged interstage home monitoring as a protective intervention. CONCLUSIONS: Although psychosocial burden before and after stage II remains high, becoming a family is an essential experience for parents and confirms their parenthood. RELEVANCE TO CLINICAL PRACTICE: Healthcare professionals must be aware of parents' needs during this vulnerable interstage period and to provide psychosocial and nursing support.
Keywords: adult; coping behavior; female; human; hypoplastic left heart syndrome; infant; male; newborn; parent; pathophysiology; physiologic monitoring; prospective study; psychology; qualitative research; quality of life; questionnaire; young adult

A national cohort study evaluating infant and fetal mortality caused by birth defects in Korea - Ko, H.S.; Kim, D.J.; Chung, Y.; Wie, J.H.; Choi, S.K.; Park, I.Y.; Park, Y.G.; Shin, J.C. (BMJ Open, 2017)
Objective To analyse the prevalence of fetal and infant deaths due to birth defects in Korea and those trends according to maternal age. Design Retrospective national cohort study Setting Korean Vital Statistics database of the Korean Statistical Information Service, between 2009 and 2015. Participants 2176 infant deaths and 4343 fetal deaths caused by birth defects, among 3 181 145 total live births and 43 385 fetal deaths during the study periods. Methods Infant and fetal mortality rates (IMRs and FMRs) by birth defects, from deaths caused by birth defects, were analysed. They were compared, according to maternal age groups: (I) ' 10-19 years'; (II) ' 20-29 years'; (III) ' 30-34 years'; (IV) ' 35-39 years'; and (V) ' 40-55 years'. Main outcome measures IMRs and FMRs by birth defects and comparison according to maternal age group. Results IMRs and FMRs by birth defects were 6.84 per 10 000 live births and 13.47 per 10 000 total births. The most common causes of infant deaths and fetal deaths by birth defect were anomaly of the circulatory system (51.1%, IMR 3.5) and chromosomal abnormality (33.1%, FMR 4.46), respectively. Among groups by maternal age, FMRs by birth defects were significantly higher in groups I and V compared with group III (OR 6.59, 95% CI 3.49 to 12.43; and OR 3.46, 95% CI 1.77 to 6.78, respectively). IMR and FMR by nervous system anomaly were significantly higher in group I at 3.63 (OR 2.0, 95% CI 1.97 to 2.03) and 29.84 (OR 15.04, 95% CI 3.59 to 62.96) compared with 0.32 and 1.97 in group III. Conclusion FMRs by birth defects were the highest in the extreme maternal age groups. Severe anomalies, except for chromosomal abnormality, were most prevalent in teenage pregnancies.
Keywords: adolescent; adult; article; cardiovascular malformation; cat cry syndrome; child; child death; chromosome aberration; cohort analysis; comparative study; congenital diaphragm hernia; congenital heart malformation; congenital malformation; controlled study; Down syndrome; Edwards syndrome; Fallot tetralogy; female; fetus; fetus death; fetus mortality; gestational age; human; hypoplastic left heart syndrome; infant; infant mortality; kleinfelter syndrome; Korea; live birth; major clinical study; maternal age; middle aged; musculoskeletal system malformation; nervous system malformation; retrospective study; sex chromosome aberration; triploidy; trisomy 13; trisomy 18; Turner syndrome; wolff hirschorn syndrome; young adult

Neonatal outcomes in fetuses with cardiac anomalies and the impact of delivery route - Parikh, L.I.; Grantz, K.L.; Iqbal, S.N.; Huang, C.-C.; Landy, H.J.; Fries, M.H.; Reddy, U.M. (American Journal of Obstetrics and Gynecology, 2017)
Background Congenital fetal cardiac anomalies compromise the most common group of fetal structural anomalies. Several previous reports analyzed all types of fetal cardiac anomalies together without individualized neonatal morbidity outcomes based on cardiac defect. Mode of delivery in cases of fetal cardiac anomalies varies greatly as optimal mode of delivery in these complex cases is unknown. Objective We sought to determine rates of neonatal outcomes for fetal cardiac anomalies and examine the role of attempted route of delivery on neonatal morbidity. Study Design Gravidas with fetal cardiac anomalies and delivery >34 weeks, excluding stillbirths and aneuploidies (n = 2166 neonates, n = 2701 cardiac anomalies), were analyzed from the Consortium on Safe Labor, a retrospective cohort study of electronic medical records. Cardiac anomalies were determined using International Classification of Diseases, Ninth Revision codes and organized based on morphology. Neonates were assigned to each cardiac anomaly classification based on the most severe cardiac defect present. Neonatal outcomes were determined for each fetal cardiac anomaly. Composite neonatal morbidity (serious respiratory morbidity, sepsis, birth trauma, hypoxic ischemic encephalopathy, and neonatal death) was compared between attempted vaginal delivery and planned cesarean delivery for prenatal and postnatal diagnosis. We used multivariate logistic regression to calculate adjusted odds ratio for composite neonatal morbidity controlling for race, parity, body mass index, insurance, gestational age, maternal disease, single or multiple anomalies, and maternal drug use. Results Most cardiac anomalies were diagnosed postnatally except hypoplastic left heart syndrome, which had a higher prenatal than postnatal detection rate. Neonatal death occurred in 8.4% of 107 neonates with conotruncal defects. Serious respiratory morbidity occurred in 54.2% of 83 neonates with left ventricular outflow tract defects. Overall, 76.3% of pregnancies with fetal cardiac anomalies underwent attempted vaginal delivery. Among patients who underwent attempted vaginal delivery, 66.1% had a successful vaginal delivery. Women with a fetal cardiac anomaly diagnosed prenatally were more likely to have a planned cesarean delivery than women with a postnatal diagnosis (31.7 vs 22.8%; P <.001). Planned cesarean delivery compared to attempted vaginal delivery was not associated with decreased composite neonatal morbidity for all prenatally diagnosed (adjusted odds ratio, 1.67; 95% confidence interval, 0.85–3.30) or postnatally diagnosed (adjusted odds ratio, 0.99; 95% confidence interval, 0.77–1.27) cardiac anomalies. Conclusion Most fetal cardiac anomalies were diagnosed postnatally and associated with increased rates of neonatal morbidity. Planned cesarean delivery for prenatally diagnosed cardiac anomalies was not associated with less neonatal morbidity.
Keywords: adult; aortic valve stenosis; Apgar score; article; body mass; cesarean section; cohort analysis; congenital heart malformation; drug use; Ebstein anomaly; electronic medical record; Fallot tetralogy; female; fetus malformation; gestational age; great vessels transposition; health insurance; heart atrium septum defect; heart left ventricle outflow tract obstruction; heart right ventricle double outlet; heart right ventricle outflow tract obstruction; heart ventricle septum defect; human; hypoplastic left heart syndrome; intermethod comparison; labor induction; live birth; lung vein drainage anomaly; major clinical study; maternal disease; newborn; newborn death; newborn morbidity; newborn mortality; obstetric delivery; parity; prenatal diagnosis; priority journal; pulmonary valve atresia; race; respiratory tract disease; retrospective study; vaginal delivery

Congenital heart disease - Puri, K.; Allen, H.D.; Qureshi, A.M. (Pediatrics in Review, 2017)
1. On the basis of clinical consensus and research observation, newborns with ductal-dependent congenital heart disease (CHD) may present with cyanosis or shock as the patent ductus arteriosus starts to close, indicating a need for prostaglandin to maintain output to the pulmonary or systemic circulation. (5)(7)(8) 2. On the basis of research evidence, as well as clinical consensus, children with acyanotic shunting lesions can present with features of congestive heart failure and require nutritional and diuretic optimization until the time of early surgical correction. (1)(2)(9) 3. On the basis of research evidence, as well as clinical consensus, children with cyanotic heart disease may undergo early corrective surgery or, in some instances, undergo palliation with a shunt (modified Blalock-Taussig-Thomas shunt) to supply pulmonary blood flow prior to their corrective surgery. (22)(32) 4. On the basis of strong clinical evidence, children who undergo single-ventricle palliation are at risk for developing complications at any stage of the palliation. (31) 5. On the basis of clinical evidence, as well as clinical consensus, although most children with corrected CHD have a normal quality of life, lifelong cardiology follow-up is needed for all of these patients to monitor the development of any long-term complications and/or sequelae. (13)(14)(20)(24)(27)(30)(39).
Keywords: diuretic agent; ibuprofen; indometacin; metoprolol; phenylephrine; spironolactone; aortic valve stenosis; arterial trunk; article; atrioventricular septal defect; clinical feature; congenital heart disease; Fallot tetralogy; general practitioner; great vessels transposition; health care; heart atrium septum defect; heart catheterization; heart valve stenosis; heart ventricle septum defect; human; immunization; lung vein drainage anomaly; newborn period; patent ductus arteriosus; pulmonic valve stenosis; pulse oximetry; subacute endocarditis; transluminal valvuloplasty; tricuspid valve atresia

A Nordic multicenter survey of long-term bowel function after transanal endorectal pull-through in 200 patients with rectosigmoid Hirschsprung disease - Bjørnland, K.; Pakarinen, M.P.; Stenstrøm, P.; Stensrud, K.J.; Neuvonen, M.; Granström, A.L.; Graneli, C.; Pripp, A.H.; Arnbjörnsson, E.; Emblem, R.; Wester, T.; Rintala, R.J. (Journal of Pediatric Surgery, 2017)
Objective Transanal endorectal pull-through (ERPT) is the most popular technique to treat Hirschsprung disease (HD). Still, there is limited knowledge on long-term bowel function. This cross-sectional, multicenter study assessed long-term bowel function in a large HD population and examined predictors of poor outcome. Methods Patients older than four years or their parents filled out a validated questionnaire on bowel function. Clinical details were recorded retrospectively from medical records. Results 73/200 (37%) patients reported absolutely no impaired bowel function, meaning no constipation, fecal accidents, stoma, appendicostomy or need for enemas. Seven (4%) had a stoma, and 33 (17%) used antegrade or rectal colonic enemas. Most disarrangements of fecal control and constipation were significantly less common in older age group, but abnormal defecation frequency and social problems remained unchanged. Syndromic patients (n = 31) experienced frequent fecal accidents (46%) more often than nonsyndromic (14%, P < 0.001). Having a syndrome (adjusted OR 5.6, 95% CI 2.1–15, P = 0.001) or a complete transanal ERPT (adjusted OR 2.4, 95% CI 1.1–5.7, P = 0.038) was significantly associated with poor outcome defined as having a stoma, an appendicostomy, daily fecal accidents or need of regular rectal wash outs. Conclusion A significant number of HD patients experience bowel problems many years after definite surgery. Fecal control was significantly better in older than younger HD patients, but some continued to have considerable bowel problems also as adults. A total transanal ERPT was associated with poorer outcome. Long-term follow-up of HD patients is warranted. Prognosis Study: Level II.
Keywords: botulinum toxin; enema; abdominal discomfort; age; anastomosis leakage; antibiotic therapy; article; child; clinical outcome; congenital central hypoventilation syndrome; constipation; cross-sectional study; defecation; Down syndrome; enterocolitis; enterostomy; feces incontinence; female; Hirschsprung disease; human; hypoplastic left heart syndrome; intestine function; intestine obstruction; lactose intolerance; major clinical study; male; medical record review; multicenter study; muscle resection; postoperative complication; predictive value; priority journal; pull through operation; retrospective study; sex difference; social problem; stoma; treatment outcome; Wilson disease; wound dehiscence; wound infection

Parenting a child at home with hypoplastic left heart syndrome: Experiences of commitment, of stress, and of love - Cantwell-Bartl, A.M.; Tibballs, J. (Cardiology in the Young, 2017)
Objective To evaluate the experiences of parenting a child with hypoplastic left heart syndrome after the child has been discharged home from hospital. Design A study of the parents' experiences using face-to-face interviews and psychometric measures with parents whose child had survived stage surgery. Setting Parents were interviewed within the home environment or within the hospital if that was their choice. Subjects A total of 29 parents (16 mothers and 13 fathers) of surviving children. Intervention A semi-structured face-to-face interview plus psychometric tests (parent demographics, Maslach Burnout Inventory, Impact on Family Scale, and the Psychological Check List-Civilian). Measurements and main results The parents' experience in supporting a child with hypoplastic left heart syndrome is one of stress, of commitment, and of love. Although parents experienced joy in their child, they were also subjected to anxiety with four parents test positive to post-traumatic stress disorder and hypervigilance while monitoring their child's condition. Parents lived with many difficulties, and demands.
Keywords: article; child care; child parent relation; controlled study; female; grief; home care; home environment; hospital discharge; human; hypoplastic left heart syndrome; interview; involuntary commitment; love; male; parental attitude; parental stress; personal experience; psychometry; semi structured interview

Neuro-developmental outcome in single-ventricle patients: is the Norwood procedure a risk factor? - Rotermann, I.; Logoteta, J.; Falta, J.; Wegner, P.; Jung, O.; Dütschke, P.; Scheewe, J.; Kramer, H.-H.; Hansen, J.H. (European journal of cardio-thoracic surgery : official journal of the European Association for Cardio-thoracic Surgery, 2017)
OBJECTIVES: Complex neonatal surgery is considered a risk factor for neuro-developmental impairment in single-ventricle patients. Neuro-developmental outcome was compared between preschool-aged Fontan patients who underwent a Norwood procedure and single-ventricle patients not requiring neonatal surgery with cardiopulmonary bypass. METHODS: Verbal, performance and full-scale intelligence quotient (IQ) were evaluated with the Wechsler Preschool and Primary Scale of Intelligence. Cognitive functions were assessed with the German 'Kognitiver Entwicklungstest für das Kindergartenalter' (KET-KID). Risk factors for impaired neuro-development were evaluated. RESULTS: Neuro-developmental assessment was completed in 95 patients (Norwood: n = 69; non-Norwood: n = 26). Median (interquartile range) IQ and KET-KID scores were in the normal range. Except for verbal KET-KID, scores did not differ between Norwood and non-Norwood patients (verbal IQ: 98 (86-105) vs 93 (85-102), P = 0.312; performance IQ: 91 (86-100) vs 96 (86-100), P = 0.932; full-scale IQ: 93 (86-101) vs 89 (84-98), P = 0.314; KET-KID verbal: 48 (17-72) vs 25 (2-54), P = 0.020; KET-KID non-verbal: 33 (18-62) vs 45 (15-54), P = 0.771; KET-KID global: 42 (14-65) vs 28 (6-63), P = 0.208). Full-scale IQ was below average (<85 points) in 14 (20%) Norwood and 9 (35%) non-Norwood cases (P = 0.181). Global KET-KID was below average (<16th percentile) in 19 (28%) and 10 (38%) patients (P = 0.326). Smaller head circumference z-score and complications before neonatal surgery were independently associated with lower scores. CONCLUSIONS: Neuro-developmental outcome of preschool-aged Fontan patients was in the normal range. The Norwood procedure was not a risk factor for neuro-developmental impairment. Preoperative condition and patient-related factors were more important determinants than variables related to surgical palliation.
Keywords: child; cognition; cognitive defect; developmental disorder; female; Germany; human; hypoplastic left heart syndrome; incidence; male; neuropsychological test; Norwood procedure; pathophysiology; physiology; preschool child; risk assessment; risk factor; treatment outcome

Pediatric cardiac transplantation - Ryan, T.D.; Chin, C. (Seminars in Pediatric Surgery, 2017)
Heart transplantation in pediatric patients generally arises as a treatment option of last resort, that is, the indication is for patients with heart failure of various etiologies, with potential or actual end-organ dysfunction, in whom there are no reasonable, long-term options for life-prolonging therapy. The concept of heart failure is complex in a pediatric population, particularly those with congenital heart disease. While heart failure may refer simply to systolic dysfunction leading to low cardiac output, it can also encompass: diastolic dysfunction in restrictive cardiomyopathy; single ventricle physiology without an option for stable palliation. A good candidate should have a predicted life expectancy less than the median lifetime of a transplanted heart. Significant improvement in survival has been observed over time with 1- and 5-year survival approximately 90% and 80% in the contemporary era.
Keywords: article; artificial ventilation; cardiopulmonary exercise test; clinical protocol; congenital heart disease; extracorporeal oxygenation; heart catheterization; heart transplantation; hospital admission; human; immunosuppressive treatment; laboratory test; patient care; patient selection; pediatrics; postoperative period; practice guideline; priority journal; social psychology; survival rate; treatment contraindication; treatment indication; treatment planning

Plasma microvesicle analysis identifies microRNA 129-5p as a biomarker of heart failure in univentricular heart disease - Ramachandran, S.; Lowenthal, A.; Ritner, C.; Lowenthal, S.; Bernstein, H.S. (PLoS ONE, 2017)
Biomarkers of heart failure in adults have been extensively studied. However, biomarkers to monitor the progression of heart failure in children with univentricular physiology are less well understood. We proposed that as mediators of diverse pathophysiology, miRNAs contained within circulating microvesicles could serve as biomarkers for the presence and progression of heart failure in univentricular patients. To test this, we studied the association of heart failure with elevations in specific miRNAs isolated from circulating microvesicles in a cohort of children with univentricular heart disease and heart failure. We conducted a single site cross-sectional observational study of 71 children aged 1 month-7 years with univentricular heart disease and heart failure. We demonstrated that levels of miR129-5p isolated from plasma microvesicles were inversely related to the degree of clinical heart failure as assessed by Ross score. We then showed that miR129-5p levels are downregulated in HL1 cells and human embryonic stem cell-derived cardiomyocytes exposed to oxidative stress. We demonstrated that bone morphogenetic protein receptor 2, which has been implicated in the development of pulmonary vascular disease, is a target of miR129-5p, and conversely regulated in response to oxidative stress in cell culture. Levels of miR129-5p were inversely related to the degree of clinical heart failure in patients with univentricular heart disease. This study demonstrates that miR129-5p is a sensitive and specific biomarker for heart failure in univentricular heart disease independent of ventricular morphology or stage of palliation. Further study is warranted to understand the targets affected by miR129-5p with the development of heart failure in patients with univentricular physiology.
Keywords: bone morphogenetic protein receptor 2; microRNA; microRNA 129 5p; unclassified drug; animal cell; article; cardiac muscle cell; child; cohort analysis; controlled study; cross-sectional study; down regulation; embryo; embryonic stem cell; female; heart disease; heart failure; human; human cell; infant; informed consent; major clinical study; male; membrane microparticle; mouse; nonhuman; observational study; oxidative stress; pathophysiology; protein RNA binding; pulmonary vascular disease; Ross score; scoring system; univentricular heart disease

Inspiratory muscle training is associated with improved inspiratory muscle strength, resting cardiac output, and the ventilatory efficiency of exercise in patients with a fontan circulation - Laohachai, K.; Winlaw, D.; Selvadurai, H.; Gnanappa, G.K.; d'Udekem, Y.; Celermajer, D.; Ayer, J. (Journal of the American Heart Association, 2017)
Background-Patients with a Fontan circulation have reduced exercise capacity and respiratory muscle strength. Inspiratory muscle training (IMT) improves exercise capacity and quality of life in adults with heart failure. We assessed whether 6 weeks of a home-based program of IMT improves inspiratory muscle strength and the ventilatory efficiency of exercise in adolescent patients with a Fontan circulation. Methods and Results-Twenty-three adolescent participants (aged 16±2 years) with a Fontan circulation underwent 6 weeks of IMT for 30 minutes daily. Respiratory muscle strength (maximal inspiratory pressure and expiratory pressure), lung function, and exercise capacity (cardiopulmonary exercise testing) were assessed. Fourteen of 23 participants also underwent exercise cardiac magnetic resonance imaging to examine the effects of IMT on cardiac output and systemic and pulmonary blood flow. Six weeks of IMT improved maximal inspiratory pressure by 36±24 cm H2O (61±46%) with no change in maximal expiratory pressure. Ventilatory efficiency of exercise improved after 6 weeks of IMT (from 34.2±7.8 to 32.2±5.6, P=0.04). In those who underwent exercise cardiac magnetic resonance imaging, IMT increased resting cardiac output (from 4.2±1.2 to 4.5±1.0 L/min, P=0.03) and ejection fraction (from 50.1±4.3 to 52.8±6.1%, P=0.03). Conclusions-Six weeks of IMT is associated with improved inspiratory muscle strength, ventilatory efficiency of exercise, and resting cardiac output in young Fontan patients. IMT may be a simple beneficial addition to the current management of Fontan patients, potentially reducing exercise intolerance and long-term morbidity and mortality.
Keywords: Ergoselect 200; Phillips Intera; adolescent; adult; article; cardiopulmonary exercise test; cardiovascular magnetic resonance; clinical article; ergometer; exercise; female; Fontan procedure; forced expiratory volume; forced vital capacity; heart ejection fraction; heart output; human; inspiratory capacity; lung blood flow; lung function; male; maximal expiratory pressure; maximal inspiratory pressure; morbidity; mortality; muscle strength; muscle training; nuclear magnetic resonance scanner; priority journal; program evaluation; respiratory function; therapy effect; Ergoselect 200; Phillips Intera

Cognitive dysfunction in adult CHD with different structural complexity - Tyagi, M.; Fteropoulli, T.; Hurt, C.S.; Hirani, S.P.; Rixon, L.; Davies, A.; Picaut, N.; Kennedy, F.; Deanfield, J.; Cullen, S.; Newman, S.P. (Cardiology in the Young, 2017)
Objective We carried out a cross-sectional study to assess cognitive function in a sample of adult CHD patients, within the Functioning in Adult Congenital Heart Disease study London. The association between cognitive functioning and disease complexity was examined. Methods A total of 310 patients participated in this study. Patients were classified into four structural complexity groups - tetralogy of Fallot, transposition of the great arteries, single ventricle, and simple conditions. Each patient underwent neuropsychological assessment to evaluate cognitive function, including memory and executive function, and completed questionnaires to assess depression and anxiety. Results Among all, 41% of the sample showed impaired performance (>1.5 SD below the normative mean) on at least three tests of cognitive function compared with established normative data. This was higher than the 8% that was expected in a normal population. The sample exhibited significant deficits in divided attention, motor function, and executive functioning. There was a significant group difference in divided attention (F=5.01, p=0.002) and the mean total composite score (F=5.19, p=0.002) between different structural complexity groups, with the simple group displaying better cognitive function. Conclusion The results indicate that many adult CHD patients display impaired cognitive function relative to a healthy population, which differs in relation to disease complexity. These findings may have implications for clinical decision making in this group of patients during childhood. Possible mechanisms underlying these deficits and how they may be reduced or prevented are discussed; however, further work is needed to draw conclusive judgements.
Keywords: adolescent; adult; age; aged; anxiety disorder; article; attention; Center for Edpidemiological Studies Short Depression Scale; clinical decision making; cognition; cognitive defect; congestive cardiomyopathy; controlled study; cross-sectional study; depression; disease association; disease classification; education; executive function; Fallot tetralogy; female; great vessels transposition; heart single ventricle; human; intelligence quotient; major clinical study; male; memory; mood; motor performance; neuropsychological test; Positive and Negative Affect Schedule; problem solving; questionnaire; Rey auditory verbal learning test; scoring system; State Trait Anxiety Inventory; verbalization; Wechsler adult intelligence scale; working memory

Fontan completion in reverse order out of necessity: Secondary Glenn after primary extracardiac inferior cavopulmonary artery connection - Dodge-Khatami, J.; Aggarwal, A.; Taylor, M.B.; Maposa, D.; Salazar, J.D.; Dodge-Khatami, A. (Cardiology in the Young, 2017)
The primary extracardiac inferior cavopulmonary connection is an unusual novel palliation for single-ventricle physiology, which we first performed in the setting of unfavourable upper-body systemic venous anatomy for a standard bi-directional Glenn, and in lieu of leaving our patient with shunt-dependent physiology. After an initial 16-month satisfactory follow-up, increasing cyanosis led to the discovery of a veno-venous collateral that was coiled, but, more importantly, to impressive growth of a previously diminutive superior caval vein, which allowed us to perform completion Fontan with a good outcome. Performing the single-ventricle staging in a reverse manner, first from below with a primary inferior cavopulmonary connection, followed by Fontan completion from above with a standard superior caval vein bi-directional Glenn, is also possible when deemed necessary.
Keywords: acetylsalicylic acid; anastomosis; article; cardiac conduit; case report; cavopulmonary connection; child; cyanosis; follow up; Fontan procedure; Glenn shunt; heart catheterization; hospitalization; human; intensive care unit; lung artery pressure; lung blood flow; outcome assessment; oxygen consumption; oxygen saturation; patient satisfaction; postoperative care; preschool child; pulmonary valve stenosis; pulse oximetry; reoperation; sternotomy; superior cava vein; weaning; body weight gain

Cardiac haemangioma associated with a duct-dependent congenital heart disease in a newborn infant - Djordjevic, S.A.; Glumac, S.; Kalanj, J. (Cardiology in the Young, 2017)
Cardiac haemangiomas are exceedingly rare; however, they can cause significant haemodynamic impairment and disturbances in heart rhythm. Rarely, cardiac tumours may also coexist with congenital heart lesions. We present an extremely unusual case of a cardiac haemangioma in the setting of complex transposition of the great arteries that caused functional tricuspid atresia. To our knowledge, this is the first such case described in the literature.
Keywords: alpha smooth muscle actin; blood clotting factor 8; platelet endothelial cell adhesion molecule 1; oxygen; prostaglandin E1; tumor protein; unclassified drug; WT 1 protein; article; autopsy; bradycardia; cardiac hemangioma; cardiogenic shock; case report; congenital heart disease; cyanosis; duct dependent congenital heart disease; dyspnea; echocardiography; first degree atrioventricular block; great vessels transposition; heart atrium septum defect; heart right left shunt; heart sound; heart tumor; heart ventricle tachycardia; hemangioma; histopathology; human; human tissue; hypoxia; immunohistochemistry; infant; intubation; male; metabolic acidosis; pulmonary valve atresia; pulse rate; ST segment; systolic heart murmur; T wave; thorax radiography; tissue oxygenation; treatment refusal; tricuspid valve atresia

Rates of autism and potential risk factors in children with congenital heart defects - Bean Jaworski, J.L.; Flynn, T.; Burnham, N.; Chittams, J.L.; Sammarco, T.; Gerdes, M.; Bernbaum, J.C.; Clancy, R.R.; Solot, C.B.; Zackai, E.H.; McDonald-McGinn, D.M.; Gaynor, J.W. (Congenital Heart Disease, 2017)
Objective: Atypical development, behavioral difficulties, and academic underachievement are common morbidities in children with a history of congenital heart defects and impact quality of life. Language and social-cognitive deficits have been described, which are associated with autism spectrum disorders. The current study aimed to assess the rates of autism spectrum disorders in a large sample of children with a history of congenital heart defects and to assess medical, behavioral, and individual factors that may be associated with the risk of autism spectrum disorders. Design: Participants included 195 children with a history of congenital heart defects, who are followed in a large-scale longitudinal study. Measures included behavioral data from 4-year-old neurodevelopmental evaluations and parent-report data from a later annual follow-up. Results: Using established cutoffs on an autism spectrum disorder screener, children with congenital heart defects showed higher rates of “possible” autism spectrum disorders than national rates, (Chi-square Test of Equal Proportions), all Ps <.05. A stepwise variable selection method was used to create a “best prediction model” and multivariable logistic regression was used to identify variables predicting diagnostic status. Factors associated with diagnostic risk included medical (delayed sternal closure, prematurity, positive genetic findings), behavioral (cognitive, language, attention issues), and individual (socioeconomic, cultural/racial) variables. ROC analyses identified a cutoff of 7 to maximize sensitivity/specificity based on parent-reported diagnosis. Conclusions: Risk of autism spectrum disorder screening status in children with congenital heart defects was higher than expected from population rates. Findings highlight the need for referral to a specialist to assess the presence and severity of social-communication issues and congenital heart defects population-specific screening thresholds for children with concern for autism spectrum disorders.
Keywords: aortic coarctation; article; attention; autism; child; cognition; congenital heart malformation; controlled study; cultural factor; Fallot tetralogy; female; great vessels transposition; heart ventricle septum defect; human; hypoplastic left heart syndrome; language; longitudinal study; major clinical study; male; prediction; prematurity; prevalence; priority journal; race; receiver operating characteristic; risk factor; sensitivity and specificity; socioeconomics

Effect of congenital heart disease on 4-year neurodevelopment within multiple-gestation births - Schultz, A.H.; Ittenbach, R.F.; Gerdes, M.; Jarvik, G.P.; Wernovsky, G.; Bernbaum, J.; Solot, C.; Clancy, R.R.; Nicolson, S.C.; Spray, T.L.; McDonald-McGinn, D.; Zackai, E.; et al. (Journal of Thoracic and Cardiovascular Surgery, 2017)
Objectives We sought to assess the effect of congenital heart disease requiring infant surgery with cardiopulmonary bypass on neurodevelopmental outcomes and growth at 4 years of age, while matching for gestational age, socioeconomic status, maternal gestational conditions, home environment, and parental intelligence by studying multiple-gestation births. Methods We performed within-family comparison of 14 multiple-gestation births in which 1 child had congenital heart disease requiring surgery with cardiopulmonary bypass at ≤6 months of age. Between 4 and 5 years of age, a comprehensive neurodevelopmental assessment was performed. Paired comparisons were conducted between siblings with and without heart defects using a series of nonparametric tests. Results On average, the children qualified as late preterm (mean gestational age 35.4 ± 2.6 weeks). At an average age of 4.8 ± 0.1 years, children with congenital heart disease weighed less than their siblings (median weight for age z score −0.4 vs 0.1, P =.02) and had worse performance for cognition (median full-scale IQ 99 vs 109, P =.02) and fine motor skills (median Wide Range Assessment of Visual Motor Ability, Fine Motor score 94.5 vs 107.5, P <.01). Conclusions After controlling for socioeconomic status, home environment, parental intelligence, and gestational factors by using multiple-gestation births, congenital heart disease requiring surgery with cardiopulmonary bypass at ≤6 months of age is associated with lower weight, cognitive abilities and fine motor skills at 4 years of age.
Keywords: apolipoprotein E; article; birth weight; cardiopulmonary bypass; child; child health care; congenital heart disease; deep hypothermic circulatory arrest; executive function; female; follow up; gestational age; head circumference; heart single ventricle; home environment; human; intelligence quotient; major clinical study; male; motor performance; nerve cell differentiation; outcome assessment; pregnancy; preschool child; priority journal; sibling; single nucleotide polymorphism; social competence; social status; surgical mortality; two ventricle heart disease

Predictors of missed appointments in patients referred for congenital or pediatric cardiac magnetic resonance - Lu, J.C.; Lowery, R.; Yu, S.; Ghadimi Mahani, M.; Agarwal, P.P.; Dorfman, A.L. (Pediatric Radiology, 2017)
Background: Congenital cardiac magnetic resonance is a limited resource because of scanner and physician availability. Missed appointments decrease scheduling efficiency, have financial implications and represent missed care opportunities. Objective: To characterize the rate of missed appointments and identify modifiable predictors. Materials and methods: This single-center retrospective study included all patients with outpatient congenital or pediatric cardiac MR appointments from Jan. 1, 2014, through Dec. 31, 2015. We identified missed appointments (no-shows or same-day cancellations) from the electronic medical record. We obtained demographic and clinical factors from the medical record and assessed socioeconomic factors by U.S. Census block data by patient ZIP code. Statistically significant variables (P<0.05) were included into a multivariable analysis. Results: Of 795 outpatients (median age 18.5 years, interquartile range 13.4–27.1 years) referred for congenital cardiac MR, a total of 91 patients (11.4%) missed appointments; 28 (3.5%) missed multiple appointments. Reason for missed appointment could be identified in only 38 patients (42%), but of these, 28 (74%) were preventable or could have been identified prior to the appointment. In multivariable analysis, independent predictors of missed appointments were referral by a non-cardiologist (adjusted odds ratio [AOR] 5.8, P=0.0002), referral for research (AOR 3.6, P=0.01), having public insurance (AOR 2.1, P=0.004), and having scheduled cardiac MR from November to April (AOR 1.8, P=0.01). Conclusion: Demographic factors can identify patients at higher risk for missing appointments. These data may inform initiatives to limit missed appointments, such as targeted education of referring providers and patients. Further data are needed to evaluate the efficacy of potential interventions.
Keywords: adolescent; adult; aortic arch anomaly; article; cardiologist; cardiomyopathy; cardiovascular magnetic resonance; congenital heart disease; electronic medical record; Fallot tetralogy; female; great vessels transposition; heart single ventricle; high risk patient; human; lung insufficiency; major clinical study; male; outpatient; patient attendance; patient care; patient referral; pediatric cardiology; pediatric hospital; priority journal; pulmonary valve stenosis; retrospective study

Building a comprehensive team for the longitudinal care of single ventricle heart defects: Building blocks and initial results - Texter, K.; Davis, J.A.M.; Phelps, C.; Cheatham, S.; Cheatham, J.; Galantowicz, M.; Feltes, T.F. (Congenital Heart Disease, 2017)
Introduction: With increasing survival of children with HLHS and other single ventricle lesions, the complexity of medical care for these patients is substantial. Establishing and adhering to best practice models may improve outcome, but requires careful coordination and monitoring. Methods: In 2013 our Heart Center began a process to build a comprehensive Single Ventricle Team designed to target these difficult issues. Results: Comprehensive Single Ventricle Team in 2014 was begun, to standardize care for children with single ventricle heart defects from diagnosis to adulthood within our institution. The team is a multidisciplinary group of providers committed to improving outcomes and quality of life for children with single ventricle heart defects, all functioning within the medical home of our heart center. Standards of care were developed and implemented in five target areas to standardize medical management and patient and family support. Under the team 100 patients have been cared for. Since 2014 a decrease in interstage mortality for HLHS were seen. Using a team approach and the tools of Quality Improvement they have been successful in reaching high protocol compliance for each of these areas. Conclusions: This article describes the process of building a successful Single Ventricle team, our initial results, and lessons learned. Additional study is ongoing to demonstrate the effects of these interventions on patient outcomes.
Keywords: article; heart center; heart single ventricle; human; longitudinal care; major clinical study; medical care; mortality; outcome assessment; patient care; priority journal; protocol compliance; quality of life; standardization; treatment outcome

May We Take Our Baby With Hypoplastic Left Heart Syndrome Home? - Devereaux, M.; Kon, A.A. (The American journal of bioethics : AJOB, 2017)
Keywords: child parent relation; education; ethics; home care; human; hypoplastic left heart syndrome; infant; newborn; palliative therapy; parental consent; patient education; prognosis; psychology; treatment withdrawal

The Ethics of Treatment for Hypoplastic Left Heart Syndrome (HLHS) - Spike, J.P. (The American journal of bioethics : AJOB, 2017)
Keywords: case report; child parent relation; contraindication; cost of illness; education; ethics; heart surgery; human; hypoplastic left heart syndrome; male; newborn; palliative nursing; prognosis; psychology; quality of life; risk assessment

Growing Discomfort With Comfort Care for Hypoplastic Left Heart Syndrome: Why We Should Still Defer to Parental Wishes - Paul, E.A.; Kohlberg, E.M.; Orfali, K. (The American journal of bioethics : AJOB, 2017)
Keywords: child parent relation; counseling; decision making; education; ethics; human; hypoplastic left heart syndrome; informed consent; medical ethics; newborn; parental consent; patient comfort; psychology; risk assessment; treatment withdrawal

Hypoplastic Left Heart Syndrome: The Case Against Palliative Surgery - Erkonen, G.E.; Hanfland, R.A. (The American journal of bioethics : AJOB, 2017)
Keywords: child parent relation; contraindication; decision making; education; ethics; heart surgery; human; hypoplastic left heart syndrome; newborn; palliative therapy; parental consent; patient education; psychology; quality of life

Longitudinal Outcomes of Patients With Single Ventricle After the Fontan Procedure - Atz, A.M.; Zak, V.; Mahony, L.; Uzark, K.; D'agincourt, N.; Goldberg, D.J.; Williams, R.V.; Breitbart, R.E.; Colan, S.D.; Burns, K.M.; Margossian, R.; Henderson, H.T.; et al. (Journal of the American College of Cardiology, 2017)
Background Multicenter longitudinal objective data for survival into adulthood of patients who have undergone Fontan procedures are lacking. Objectives This study sought to describe transplant-free survival and explore relationships between laboratory measures of ventricular performance and functional status over time. Methods Exercise testing, echocardiography, B-type natriuretic peptide, functional health assessment, and medical history abstraction were repeated 9.4 ± 0.4 years after the Fontan Cross-Sectional Study (Fontan 1) and compared with previous values. Cox regression analysis explored risk factors for interim death or cardiac transplantation. Results From the original cohort of 546 subjects, 466 were contacted again, and 373 (80%) were enrolled at 21.2 ± 3.5 years of age. Among subjects with paired testing, the percent predicted maximum oxygen uptake decreased (69 ± 14% vs. 61 ± 16%; p < 0.001; n = 95), ejection fraction decreased (58 ± 11% vs. 55 ± 10%; p < 0.001; n = 259), and B-type natriuretic peptide increased (median [interquartile range] 13 [7 to 25] pg/mol vs. 18 [9 to 36] pg/mol; p < 0.001; n = 340). At latest follow-up, a lower Pediatric Quality of Life Inventory physical summary score was associated with poorer exercise performance (R2 adjusted = 0.20; p < 0.001; n = 274). Cumulative complications since the Fontan procedure included additional cardiac surgery (32%), catheter intervention (62%), arrhythmia treatment (32%), thrombosis (12%), and protein-losing enteropathy (8%). Since Fontan 1, 54 subjects (10%) have received a heart transplant (n = 23) or died without transplantation (n = 31). The interval risk of death or/cardiac transplantation was associated with poorer ventricular performance and functional health status assessed at Fontan 1, but it was not associated with ventricular morphology, the subject's age, or the type of Fontan connection. Conclusions Interim transplant-free survival over 12 years in this Fontan cohort was 90% and was independent of ventricular morphology. Exercise performance decreased and was associated with worse functional health status. Future interventions might focus on preserving exercise capacity. (Relationship Between Functional Health Status and Ventricular Performance After Fontan—Pediatric Heart Network; NCT00132782)
Keywords: NCT00132782; brain natriuretic peptide; adolescent; age distribution; article; cardiovascular function; cardiovascular mortality; cardiovascular risk; child; echocardiography; exercise; exercise test; female; Fontan procedure; functional status; health status; heart ejection fraction; heart single ventricle; heart transplantation; heart ventricle function; human; longitudinal study; major clinical study; male; outcome assessment; oxygen consumption; priority journal; quality of life assessment; risk assessment; survival; transplant free survival

Strategies to Prevent Cast Formation in Patients with Plastic Bronchitis Undergoing Heart Transplantation - Parent, J.J.; Darragh, R.K.; Gossett, J.G.; Ryan, T.D.; Villa, C.R.; Lorts, A.; Jefferies, J.L.; Towbin, J.A.; Chin, C. (Pediatric Cardiology, 2017)
Plastic bronchitis, a rare complication after Fontan palliation, carries a high morbidity and mortality risk. Heart transplantation is an effective treatment option, but casts may occur in the early post-operative period. We present a case series detailing peri-operative management strategies to minimize morbidity and mortality related to plastic bronchitis in patients undergoing heart transplantation. Patient 1 received no treatment pre-, intra-, or post-transplant for prevention of bronchial casts and developed severe respiratory acidosis 18 h following transplant. Emergent bronchoscopy was performed and a large obstructive cast was removed. The patient recovered and received inhaled tissue plasminogen activator (tPA) for 5 days. Patient 2 received inhaled tPA before, during, and for 5 days after transplantation and no bronchial casts developed. Patient 3 underwent intraoperative bronchoscopy just prior to implantation revealing no casts. The patient underwent non-urgent, preemptive bronchoscopy on post-transplant days 1, 3, and 4, removing several partially obstructive bronchial blood clots/casts, with no casts thereafter. Heart transplantation results in eventual resolution of plastic bronchitis. Residual bronchial casts can still be problematic in the peri-operative period. Airway clearance with inhaled tPA or bronchoscopy may prevent the need for prolonged mechanical ventilation and reduce post-operative morbidity in this unique population.
Keywords: budesonide; dornase alfa; salbutamol; tissue plasminogen activator; article; breathing exercise; bronchitis; bronchoscopy; case report; child; female; heart transplantation; human; lung clearance; male; morbidity; outpatient care; plastic bronchitis; postoperative hemorrhage; preschool child; quality of life; respiratory acidosis; risk factor; school child; treatment duration

Functional Status and Quality of Life in Survivors of Extracorporeal Membrane Oxygenation After the Norwood Operation - Friedland-Little, J.M.; Uzark, K.; Yu, S.; Lowery, R.; Aiyagari, R.; Hirsch-Romano, J.C. (Annals of Thoracic Surgery, 2017)
Background Infants who require extracorporeal membrane oxygenation (ECMO) support after a Norwood operation are at increased risk for early and late death compared with patients who do not require ECMO post-Norwood. Little is known about the effect that ECMO post-Norwood has on functional status and quality of life among long-term survivors. Methods We prospectively evaluated functional status and health-related quality of life in 12 surviving patients (cases) and 19 corresponding patients (controls) from a previous retrospective case-control assessment of long-term survival in patients requiring ECMO post-Norwood. Functional status was assessed with the Vineland Adaptive Behavior Scale-II, and health-related quality of life was assessed with the Pediatric Quality of Life Inventory (PedsQL) core and cardiac modules. Results There were no differences in demographics, extracardiac or genetic anomalies, or age at follow-up assessment between ECMO cases and non-ECMO controls. The Vineland Adaptive Behavior Scale-II scores were comparable between groups, with both groups demonstrating function in the normal range in all four domains tested. The only difference in PedsQL scores between cases and controls was perceived physical appearance, which was lower among ECMO survivors by both patient and proxy report. PedsQL scores of both groups were comparable to published scores for patients with single-ventricle congenital heart disease but generally lower than scores for the healthy population. Conclusions The requirement for ECMO support after a Norwood operation does not appear to significantly affect functional status or quality of life among the subset of patients who achieve long-term survival.
Keywords: adolescent; article; child; clinical article; controlled clinical trial; controlled study; extracorporeal oxygenation; female; functional assessment; functional status; human; long term survival; male; Norwood procedure; physical appearance; priority journal; prospective study; quality of life; quality of life assessment; self evaluation; social interaction

Feasibility of exercise stress echocardiography and myocardial response in patients with repaired congenital heart disease - Hasan, B.S.; Lunze, F.I.; Alvi, N.; Shafer, K.M.; Rhodes, J. (American Heart Journal, 2017)
Background Exercise stress echocardiography (ESE) can unmask ventricular dysfunction in asymptomatic patients with congenital heart disease (CHD), but its acquisition and interpretation is often challenging, and the method has not been validated in CHD. This study aimed to evaluate the feasibility of ESE using Doppler imaging and to assess myocardial response to exercise in patients with biventricular (BiV) and univentricular (UniV) circulation after CHD repair. Methods In this single-center prospective study, we recruited 55 participants (17 females), median age 14 years (8-22 years). Our analysis categorized participants in these three groups: with structurally normal hearts as controls (n = 21), with BiV circulation (n = 20) and with UniV circulation (n = 14). We acquired ESE images of the systemic ventricle including pulsed-wave flow and spectral tissue Doppler imaging (TDI) of lateral free wall before and immediately after standard, symptom-limited exercise tests on an electronically braked cycle ergometer. Results During ESE we obtained inflow E-wave and TDI systolic (S′) and early diastolic (E′) velocities in 93% to 100% of participants at rest and in 90% to 100% of participants post exercise. Feasibility to obtain Doppler imaging parameter was the same across study groups. The myocardial response to exercise was increase in heart rate (HR), S′ and inflow E-wave velocity in all participants. Patients with BiV circulation had preserved ventricular function at rest. While patients with UniV circulation had low S′, E′, and E-wave velocities at rest in comparison to controls and to BiV group (all P < .001), both patients with BiV and UniV circulation showed significant increases in HR, S′ velocity and inflow E-wave velocity post exercise, with magnitudes of these increases higher in controls than in the BiV and UniV group. The S′ and E′ velocities were strongly associated with lower percent predicted peak oxygen consumption VO2 (rs = 0.614 and rs = 0.64, respectively, both P < .001). Conclusion ESE with Doppler imaging is a practical noninvasive diagnostic method and sufficiently robust for the assessment of morphologic LV/systemic ventricles under exercise in patients after biventricular and univentricular CHD repair. Although patients with BiV and UniV circulation had both preserved myocardial response to exercise, the magnitude of this response was the lowest in patients with UniV circulation.
Keywords: adolescent; adult; anaerobic threshold; article; bicuspid aortic valve; cardiac muscle; child; clinical article; cohort analysis; congenital heart disease; cross-sectional study; exercise; exercise tolerance; Fallot tetralogy; female; heart atrioventricular valve; heart cycle; heart function; heart left ventricle ejection fraction; heart left ventricle function; heart muscle oxygen consumption; heart rate; heart surgery; human; hypoplastic left heart syndrome; left ventricular diastolic dysfunction; male; mitral valve; priority journal; prospective study; pulsed Doppler ultrasonography; stress echocardiography; tissue Doppler imaging

Hepatic Malignancy in an Infant with Wolf–Hirschhorn Syndrome - Rutter, S.; Morotti, R.A.; Peterec, S.; Gallagher, P.G. (Fetal and Pediatric Pathology, 2017)
Introduction: Wolf–Hirschhorn syndrome (WHS) is a contiguous gene syndrome involving deletions of the chromosome 4p16 region associated with growth failure, characteristic craniofacial abnormalities, cardiac defects, and seizures. Case Report: This report describes a six-month-old girl with WHS with growth failure and typical craniofacial features who died of complex congenital heart disease. Genetic studies revealed a 9.8 Mb chromosome 4p-terminal deletion. At autopsy, the liver was grossly unremarkable. Routine sampling and histologic examination revealed two hepatocellular nodular lesions with expanded cell plates and mild cytologic atypia. Immunohistochemical staining revealed these nodules were positive for glutamine synthetase and glypican 3, with increased Ki-67 signaling and diffuse CD34 expression in sinusoidal endothelium. These findings are consistent with hepatoblastoma or hepatocellular carcinoma. Conclusions: A possible association between WHS and hepatic malignancy may be an important consideration in the care and management of WHS patients.
Keywords: CD34 antigen; glutamate ammonia ligase; glypican 3; Ki 67 antigen; prostaglandin; amnion fluid analysis; anterior fontanel; article; ascending aorta; auricle; autopsy; bicuspid aortic valve; birth weight; body height; case report; chromosome 4p; chromosome deletion 4; chronic lung disease; clinical feature; drug withdrawal; female; fetus karyotyping; follicle cyst; follow up; forehead; gestational age; growth disorder; head circumference; heart arrest; heart atrium septum defect; heart left ventricle hypertrophy; hepatoblastoma; human; human tissue; hyperbilirubinemia; hypercalcemia; hyperparathyroidism; hypertelorism; immunohistochemistry; infant; intrauterine growth retardation; liver cell carcinoma; liver histology; low set ear; lung blood flow; lung congestion; lung edema; Meckel diverticulum; micrognathia; palpebral fissure; priority journal; pulmonary valve atresia; signal transduction; tricuspid valve atresia; ventilator associated pneumonia; Wolf Hirschhorn syndrome

Reducing variation in feeding newborns with congenital heart disease - Simsic, J.M.; Carpenito, K.-R.; Kirchner, K.; Peters, S.; Miller-Tate, H.; Joy, B.; Galantowicz, M. (Congenital Heart Disease, 2017)
Objective: Enteral feeding is associated with decreased infection rates, decreased mechanical ventilation, decreased hospital length of stay, and improved wound healing. Enteral feeding difficulties are common in congenital heart disease. Our objective was to develop experience-based newborn feeding guidelines for the initiation and advancement of enteral feeding in the cardiothoracic intensive care unit. Design: This is a retrospective analysis of a quality improvement project. Setting: This quality improvement project was performed in a cardiothoracic intensive care unit. Patients: Newborns admitted to the cardiothoracic intensive care unit for cardiac surgery from January 2011 to May 2015 were retrospectively reviewed. Intervention: Newborn feeding guidelines for the initiation and advancement of enteral feeding were implemented in January 2012. Outcome measures: Guideline compliance and clinical variables before and after guideline implementation were reviewed. Results: Compliance with the guidelines increased from 83% in 2012 to 100% in the first two quarters of 2015. Preguidelines (January 2011–December 2011): 45 newborns underwent cardiac surgery; 8 deaths prior to discharge; 1 patient discharged from NICU, therefore, N = 36. Postguidelines (January 2012–May 2015): 131 newborns with 12 deaths, 12 admitted from home, 8 in the NICU, 3 on the floor preop, and 3 back transferred, therefore, N = 93. No difference in feeding preop (post 75% vs pre 69%; P =.5) or full po feeds at discharge (post 78% vs pre 89%; P =.2). Mesenteric ischemia was not statistically different postguidelines (post 6% vs pre 14%; P =.14). Length of hospital stay decreased postguidelines (post 27 + 17 d vs pre 34 + 42 d; P <.001). Conclusions: Implementation of experience-based newborn feeding guidelines for initiation and advancement of enteral feeding in the cardiothoracic intensive care unit was successful in reducing practice variation supported by increasing guideline compliance. Percentage of patient's full oral feeding at discharge did not change. Length of hospital stay was reduced although cannot be fully attributed to feeding guideline implementation.
Keywords: aortic arch anomaly; aortic coarctation; article; cardiac surgery intensive care unit; child nutrition; congenital heart disease; controlled study; enteric feeding; heart surgery; hospital admission; hospital discharge; human; hypoplastic left heart syndrome; length of stay; lung vein drainage anomaly; major clinical study; mesenteric ischemia; neonatal intensive care unit; newborn; newborn death; postoperative period; practice guideline; preoperative care; priority journal; protocol compliance; pulmonary valve atresia; retrospective study; total quality management; tricuspid valve atresia

Neurodevelopmental Outcome in Children after Fetal Cardiac Intervention for Aortic Stenosis with Evolving Hypoplastic Left Heart Syndrome - Laraja, K.; Sadhwani, A.; Tworetzky, W.; Marshall, A.C.; Gauvreau, K.; Freud, L.; Hass, C.; Dunbar-Masterson, C.; Ware, J.; Lafranchi, T.; Wilkins-Haug, L.; Newburger, J.W. (Journal of Pediatrics, 2017)
Objective To characterize neurodevelopmental outcomes after fetal aortic valvuloplasty for evolving hypoplastic left heart syndrome and determine the risk factors for adverse neurodevelopment. Study design Questionnaires were mailed to families of children who underwent fetal aortic valvuloplasty from 2000 to 2012, and medical records were reviewed retrospectively. The primary outcome was the General Adaptive Composite score of the Adaptive Behavior Assessment System Questionnaire-Second Edition. Other questionnaires included the Behavior Assessment System for Children, Behavior Rating Inventory of Executive Function, Ages and Stages, and Pediatric Quality of Life Inventory. Results Among 69 eligible subjects, 52 (75%) completed questionnaires at median age of 5.5 (range 1.3-12) years; 30 (58%) had biventricular status circulation. The General Adaptive Composite mean score (92±17) was lower than population norms (P<.001) and similar to published reports in patients with hypoplastic left heart syndrome without fetal intervention; scores in the single ventricular versus biventricular group were 97±19 vs 89±14, respectively (P=.10). On multivariable analysis, independent predictors of a lower General Adaptive Composite score were total hospital duration of stay in the first year of life (P=.001) and, when forced into the model, biventricular status (P=.02). For all other neurodevelopmental questionnaires (Behavior Assessment System for Children, Behavior Rating Inventory of Executive Function, Ages and Stages, Pediatric Quality of Life Inventory), most subscale scores for patients with biventricular and single ventricular status were similar. Conclusion Children who underwent fetal aortic valvuloplasty have neurodevelopmental delay, similar to patients with hypoplastic left heart syndrome without fetal intervention. Achievement of biventricular circulation was not associated with better outcomes. We infer that innate patient factors and morbidity during infancy have the greatest effect on neurodevelopmental outcomes.
Keywords: adaptive behavior; aortic stenosis; aortic valve repair; article; behavior assessment; Behavior Assessment System for Children; behavior rating inventory of executive function; child; cohort analysis; cross-sectional study; female; General Adaptive Composite score; heart single ventricle; human; hypoplastic left heart syndrome; length of stay; major clinical study; male; nervous system development; outcome assessment; palliative therapy; Pediatric Quality of Life Inventory; priority journal; quality of life assessment; retrospective study

Hybrid Palliation for Interrupted Aortic Arch With Small Aortic Valve - Uno, Y.; Masuoka, A.; Hotoda, K.; Katogi, T.; Suzuki, T. (World Journal for Pediatric and Congenital Heart Surgery, 2017)
Objectives: Open heart surgery for interrupted aortic arch in the neonatal period is still a high-risk procedure related in part to patient factors such as low birth weight, other morphologic anomalies, and, especially, small aortic valve size. Recently, we performed hybrid palliation with bilateral pulmonary artery banding and ductal stenting as the first-stage palliation for such cases. In this study, the outcomes of this procedure were examined. Methods: Six cases of interrupted aortic arch with a small aortic valve underwent the hybrid procedure in the neonatal period in our institute from 2010 to 2015 (mean age: 6.8 days, mean body weight: 3.2 kg, mean z score of the aortic valve annulus: −8.3). Their postoperative clinical courses and results of the second-stage surgery were evaluated. Results: No mortality or severe morbidity was seen in association with initial hybrid palliation. Five of six patients were discharged from the hospital; the one exception had a significant urinary tract anomaly. None needed an additional catheter intervention or surgical procedure postoperatively. All surviving patients underwent second-stage surgery; three had biventricular repair by the conventional method or Damus-Kaye-Stansel anastomosis with the Rastelli procedure and the other three proceeded toward staged Fontan reconstruction. Growth of the aortic valve was seen in four patients, and increased indexed left ventricle volume was recognized in one after the palliation. Conclusion: Hybrid palliation could be useful not only to avoid high-risk neonatal surgery but also to allow for eventual selection of the second-stage surgery based on the observations of potential interval development of left ventricular structures.
Keywords: anxiety; aortic arch surgery; article; bariatric surgery; echocardiography; female; follow up; heart ventricle septum defect; hospital; human; male; newborn; priority journal; respiratory tract infection; retrospective study; scoring system; subvalvular aortic stenosis; thorax radiography

Practice trends over time in the care of infants with hypoplastic left heart syndrome: A report from the National Pediatric Cardiology Quality Improvement Collaborative - Carlo, W.F.; Cnota, J.F.; Dabal, R.J.; Anderson, J.B. (Congenital Heart Disease, 2017)
Objective: The National Pediatric Cardiology Quality Improvement Collaborative (NPC-QIC) was established in 2008 to improve outcomes of hypoplastic left heart syndrome (HLHS) during the interstage period. They evaluated changes in patient variables and practice variation between early and late eras. Design: Data including demographic, operative, discharge, and follow-up variables from the first 100 patients (6/2008–1/2010) representing 18 centers were compared with the most recent 100 patients (1/2014–11/2014) from these same centers. Results: Prenatal diagnosis increased from 69% to 82% (P =.05). There were no differences in gestational age or weight at Norwood. A composite of any preoperative risk factor occurred more frequently in the early era (59% vs. 34%, P <.01). While mean age at Norwood was similar (8.3 vs. 6.6 days, P =.2), the standard deviation was significantly lower in the recent era (10.4–6.4 days, P =.04). Use of RV-PA conduit increased (67%–84%, P <.01). Rates of complete discharge communication with both the primary care physician (31%–97%, P <.01) and primary cardiologist (44%–97%, P <.01) increased substantially. There were limited changes in feeding strategies. Use of home monitoring program increased (76%–99%, P <.01) with all participants in the late era monitoring both oxygen saturation and weight. Conclusions: Among NPC-QIC centers contributing patients to both eras, there were significant changes in preoperative risk factors, surgical strategy, discharge communication, and interstage care. Further study is required to determine an association between these changes and decreased mortality.
Keywords: article; body weight; cohort analysis; controlled study; doctor patient relationship; follow up; gestational age; home monitoring; hospital discharge; human; hypoplastic left heart syndrome; infant; infant care; major clinical study; Norwood procedure; oxygen saturation; practice guideline; prenatal diagnosis; preoperative period; priority journal; right ventricle to pulmonary artery conduit; risk factor; trend study

Practices and Attitudes of Canadian Cardiologists Caring for Patients With Trisomy 18 - Young, A.A.; Simpson, C.; Warren, A.E. (Canadian Journal of Cardiology, 2017)
Trisomy 18 (T18) is a genetic disorder with cardiac lesions in up to 90% of patients. Cardiac surgery is not frequently offered because of the overall poor prognosis, although this has recently been challenged. Our study aimed to explore the practices and attitudes of Canadian pediatric cardiologists managing T18 patients. We administered a survey to pediatric cardiologists attending the Canadian Cardiovascular Congress, Canadian Pediatric Cardiology Association Business Meeting. There were 30 respondents. Most (67%) supported comfort care for affected patients with a heart lesion. None supported palliative surgery for those with complex heart lesions. Of 30 respondents, 16 (53%) counsel families prenatally, and none would present the option of a single ventricle surgical track for complex heart disease. In a hypothetical situation in which their own child was born with T18, 67% would choose comfort care with medical treatment of heart failure, and none would choose palliative surgery. Being a parent was associated with a higher likelihood of choosing termination (14 of 20 vs 6 of 9; P = 0.046) or comfort care (14 of 20 vs 6 of 9; P = 0.036). Qualitative data suggest support for comfort care, while recognizing the need for individualization and shared decision-making, within the context of institution-specific policies. Canadian pediatric cardiologists surveyed support comfort care and medical treatment but not surgical treatment for T18 patients with cardiac lesions. They place primacy on nonmaleficence, yet also recognize the emerging need for individualized shared decision-making in these cases.
Keywords: adult; aged; article; Canadian; cardiac patient; cardiologist; clinical article; female; heart injury; human; individualization; long term survival; male; medical practice; palliative therapy; patient care; patient comfort; physician attitude; prognosis; shared decision making; trisomy 18

Preschool Neurodevelopmental Outcomes in Children with Congenital Heart Disease - Brosig, C.L.; Bear, L.; Allen, S.; Hoffmann, R.G.; Pan, A.; Frommelt, M.; Mussatto, K.A. (Journal of Pediatrics, 2017)
Objective To describe preschool neurodevelopmental outcomes of children with complex congenital heart disease (CHD), who were evaluated as part of a longitudinal cardiac neurodevelopmental follow-up program, as recommended by the American Heart Association and the American Academy of Pediatrics, and identify predictors of neurodevelopmental outcomes in these children. Study design Children with CHD meeting the American Heart Association/American Academy of Pediatrics high-risk criteria for neurodevelopmental delay were evaluated at 4-5 years of age. Testing included standardized neuropsychological measures. Parents completed measures of child functioning. Scores were compared by group (single ventricle [1V]; 2 ventricles [2V]; CHD plus known genetic condition) to test norms and classified as: normal (within 1 SD of mean); at risk (1-2 SD from mean); and impaired (>2 SD from mean). Results Data on 102 patients were analyzed. Neurodevelopmental scores did not differ based on cardiac anatomy (1V vs 2V); both groups scored lower than norms on fine motor and adaptive behavior skills, but were within 1 SD of norms. Patients with genetic conditions scored significantly worse than 1V and 2V groups and test norms on most measures. Conclusions Children with CHD and genetic conditions are at greatest neurodevelopmental risk. Deficits in children with CHD without genetic conditions were mild and may not be detected without formal longitudinal testing. Parents and providers need additional education regarding the importance of developmental follow-up for children with CHD.
Keywords: adaptive behavior; article; child; child development; congenital heart disease; female; human; language ability; longitudinal study; major clinical study; male; mental development; motor performance; preschool child; priority journal; social adaptation; spelling

Aberrant Right Subclavian Artery: Correlation Between Fetal and Neonatal Abnormalities and Abnormal Genetic Screening or Testing - Ranzini, A.C.; Hyman, F.; Jamaer, E.; van Mieghem, T. (Journal of ultrasound in medicine : official journal of the American Institute of Ultrasound in Medicine, 2017)
OBJECTIVES: To determine whether fetuses with an isolated aberrant course of the right subclavian artery (ARSA) have increased risk for chromosomal abnormalities, including trisomy 21 or 22q11 deletion. METHODS: We performed a retrospective chart review of all fetuses with antenatally diagnosed ARSA. Data were collected from fetal anatomic surveys, fetal echocardiograms, noninvasive trisomy 21 screening programs, invasive genetic studies, and neonatal records. RESULTS: Seventy-nine fetuses with ARSA were identified at 20.3 ± 3.8 weeks' gestation. Forty-eight fetuses underwent chromosomal evaluation. Of those, seven had trisomy 21. Four other fetuses had unusual karyotype abnormalities. All fetuses with genetic anomalies had additional aberrant ultrasound findings. There were three spontaneous fetal deaths (trisomy 21-2 and Wolf-Hirshhorn-1). Nine pregnancies were terminated because of abnormalities and one died as a result of hypoplastic left heart syndrome. No neonate was found or suspected to have 22q11.2 deletion. The ARSA was isolated in 43 fetuses; all had unremarkable neonatal outcomes, and none were readmitted within 6 months after discharge. CONCLUSIONS: As an apparently isolated finding, ARSA is benign and not associated with trisomy 21 or 22q11.2 deletion. The finding of ARSA, however, warrants a detailed fetal ultrasound. All fetuses with ARSA and genetic anomalies had additional ultrasound findings.
Keywords: abnormalities; aneurysm; cardiovascular malformation; complication; diagnostic imaging; Down syndrome; echocardiography; embryology; female; fetus echography; genetic screening; human; male; newborn; pregnancy; procedures; retrospective study; subclavian artery

Interstage Home Monitoring After Newborn First-Stage Palliation for Hypoplastic Left Heart Syndrome: Family Education Strategies - Nieves, J.A.; Uzark, K.; Rudd, N.A.; Strawn, J.; Schmelzer, A.; Dobrolet, N. (Critical care nurse, 2017)
Children born with hypoplastic left heart syndrome are at high risk for serious morbidity, growth failure, and mortality during the interstage period, which is the time from discharge home after first-stage hypoplastic left heart syndrome palliation until the second-stage surgical intervention. The single-ventricle circulatory physiology is complex, fragile, and potentially unstable. Multicenter initiatives have been successfully implemented to improve outcomes and optimize growth and survival during the interstage period. A crucial focus of care is the comprehensive family training in the use of home surveillance monitoring of oxygen saturation, enteral intake, weight, and the early recognition of "red flag" symptoms indicating potential cardiopulmonary or nutritional decompensation. Beginning with admission to the intensive care unit of the newborn with hypoplastic left heart syndrome, nurses provide critical care and education to prepare the family for interstage home care. This article presents detailed nursing guidelines for educating families on the home care of their medically fragile infant with single-ventricle circulation.
Keywords: adult; ambulatory monitoring; caregiver; education; family; female; home care; human; hypoplastic left heart syndrome; infant; intensive care; male; middle aged; newborn; nurse attitude; nursing; organization and management; practice guideline; procedures; retrospective study

Intracoronary cardiac progenitor cells in single ventricle physiology: the perseus (cardiac progenitor cell infusion to treat univentricular heart disease) randomized phase 2 trial - Ishigami, S.; Ohtsuki, S.; Eitoku, T.; Ousaka, D.; Kondo, M.; Kurita, Y.; Hirai, K.; Fukushima, Y.; Baba, K.; Goto, T.; Horio, N.; Kobayashi, J.; et al. (Circulation Research, 2017)
Rationale: Patients with single ventricle physiology are at high risk of mortality resulting from ventricular dysfunction. The preliminary results of the phase 1 trial showed that cardiosphere-derived cells (CDCs) may be effective against congenital heart failure. Objective: To determine whether intracoronary delivery of autologous CDCs improves cardiac function in patients with single ventricle physiology. Methods and Results: We conducted a phase 2 randomized controlled study to assign in a 1:1 ratio 41 patients who had single ventricle physiology undergoing stage 2 or 3 palliation to receive intracoronary infusion of CDCs 4 to 9 weeks after surgery or staged reconstruction alone (study A). The primary outcome measure was to assess improvement in cardiac function at 3-month follow-up. Four months after palliation, controls had an alternative option to receive late CDC infusion on request (study B). Secondary outcomes included ventricular function, heart failure status, somatic growth, and health-related quality of life after a 12-month observation. At 3 months, the absolute changes in ventricular function were significantly greater in the CDC-treated group than in the controls (+6.4% [SD, 5.5] versus +1.3% [SD, 3.7]; P=0.003). In study B, a late CDC infusion in 17 controls increased the ventricular function at 3 months compared with that at baseline (38.8% [SD, 7.7] versus 34.8% [SD, 7.4]; P<0.0001). At 1 year, overall CDC infusion was associated with improved ventricular function (41.4% [SD, 6.6] versus 35.0% [SD, 8.2]; P<0.0001) and volumes (P<0.001), somatic growth (P<0.0001) with increased trophic factors production, such as insulin-like growth factor-1 and hepatocyte growth factor, and quality of life, along with a reduced heart failure status (P<0.0001) and cardiac fibrosis (P=0.014) relative to baseline. Conclusions: Intracoronary infusion of CDCs after staged palliation favorably affected cardiac function by reverse remodeling in patients with single ventricle physiology. This impact may improve heart failure status, somatic growth, and quality of life in patients and reduce parenting stress for their families. Clinical Trial Registration: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01829750.
Keywords: NCT01829750; amiodarone; scatter factor; somatomedin C; article; body growth; cardiac stem cell; cell therapy; child; clinical article; clinical outcome; controlled study; female; heart ejection fraction; heart failure; heart function; heart muscle compliance; heart muscle fibrosis; heart performance; heart proarrhythmia; heart single ventricle; heart ventricle function; human; human cell; male; open study; phase 2 clinical trial; priority journal; quality of life; quantitative analysis; randomized controlled trial

Health-related quality of life in children with surgery for CHD: A study from the Swedish National Registry for Congenital Heart Disease - Svensson, B.; Idvall, E.; Nilsson, F.; Liuba, P. (Cardiology in the Young, 2017)
Background As survival of children with CHD needing surgery has improved significantly, the need for follow-up in terms of health-related quality of life has become increasingly important. In this study, we sought to describe health-related quality of life in children with CHD in relation to cardiac surgery. Methods A retrospective Swedish National Registry for Congenital Heart Disease survey measured using DISABKIDS chronic generic measure-short version included 337 children (age 9-17 years; 39% girls). The majority (n=319, 95%) of children had a biventricular heart, whereas the remaining had a univentricular heart. Cardiac surgery was performed in 197 (58%) children. Health-related quality of life was expressed as total score (100 highest) and given as medians and 10-90th percentiles. Results The overall total score was 95 (88-100). Children with a biventricular heart who had undergone three or more surgeries (n=31; 9%) had the lowest total score of 81 (61-97; p<0.001). Children with two or more surgeries and those with univentricular heart were classified in NYHA II more frequently than children with one or no cardiac surgery (p=0.005 and <0.001, respectively). Children with three or more surgeries and those with univentricular heart needed more help at school (p<0.001). Compared with children with other chronic diseases, children with CHD had a high total score except for children with three or more surgeries who had comparable total scores with children with other chronic diseases. Conclusion Children with three or more cardiac surgeries and those with a univentricular heart appear to have lower health-related quality of life, cognitive ability, and NYHA classification.
Keywords: cardiovascular agent; adolescent; article; biventricular heart; child; chronic disease; congenital heart disease; controlled study; disease registry; female; health survey; heart single ventricle; heart surgery; human; major clinical study; male; mental capacity; patient coding; quality of life; retrospective study; school child; school health service; scoring system; Sweden

Neurocognitive functioning in adults with congenital heart disease - Ilardi, D.; Ono, K.E.; McCartney, R.; Book, W.; Stringer, A.Y. (Congenital Heart Disease, 2017)
Objective: Adults with congenital heart disease (CHD) are at increased risk of psychological disorders and cognitive deficiencies due to structural/acquired neurological abnormalities and neurodevelopmental disorders as children. However, limited information is known about the neuropsychological functioning of adults with CHD. This study screened neuropsychological abilities and explored group differences related to cardiac disease severity and neurological risk factors in adults with CHD. Design: Participants completed brief neuropsychological testing. Information about neurobehavioral and psychological symptoms, employment, education, and disability were also collected from the patient and a family member. Results: Forty-eight participants with adult CHD completed neuropsychological testing. Visuospatial skills and working memory were worse than expected compared to the typical population. Frequency of neurological comorbidities (e.g., stroke, seizures) was higher in those with more severe heart disease (e.g., single ventricle or cyanotic disease), and executive functioning was weaker in those with neurological comorbidities. Those with more severe heart disease were more likely to be unemployed and to receive disability benefits, but educational attainment did not differ. Those who received disability performed worse on tasks of executive functioning. Conclusions: Findings suggest concerns about neuropsychological functioning that need to be more comprehensively assessed in adults with CHD. Understanding the cognitive limitations of this aging population can help guide access to resources, transition of care, and medical care engagement, thus improving quality of care and quality of life.
Keywords: adult; aging; article; cerebrovascular accident; clinical article; cognition; comorbidity; congenital heart disease; controlled study; cyanotic heart disease; depth perception; disability; disease severity; education; employment; executive function; family; female; health care quality; heart disease; heart single ventricle; human; male; mental disease; neurologic disease; neuropsychological test; patient; quality of life; resource allocation; risk factor; screening; seizure; transitional care; unemployment; working memory; young adult

Perioperative Near-Infrared Spectroscopy Monitoring in Neonates with Congenital Heart Disease: Relationship of Cerebral Tissue Oxygenation Index Variability with Neurodevelopmental Outcome - Spaeder, M.C.; Klugman, D.; Skurow-Todd, K.; Glass, P.; Jonas, R.A.; Donofrio, M.T. (Pediatric Critical Care Medicine, 2017)
Objectives: To evaluate the value of perioperative cerebral near-infrared spectroscopy monitoring using variability analysis in the prediction of neurodevelopmental outcomes in neonates undergoing surgery for congenital heart disease. Design: Retrospective cohort study. Setting: Urban, academic, tertiary-care children's hospital. Patients: Neonates undergoing surgery with cardiopulmonary bypass for congenital heart disease. Interventions: Perioperative monitoring of continuous cerebral tissue oxygenation index by near-infrared spectroscopy and subsequent neurodevelopmental testing at 6, 15, and 21 months of age. Measurements and Main Results: We developed a new measure, cerebral tissue oxygenation index variability, using the root mean of successive squared differences of averaged 1-minute cerebral tissue oxygenation index values for both the intraoperative and first 24-hours postoperative phases of monitoring. There were 62 neonates who underwent cerebral tissue oxygenation index monitoring during surgery for congenital heart disease and 44 underwent subsequent neurodevelopmental testing (12 did not survive until testing and six were lost to follow-up). Among the 44 monitored patients who underwent neurodevelopmental testing, 20 (45%) had abnormal neurodevelopmental indices. Patients with abnormal neurodevelopmental indices had lower postoperative cerebral tissue oxygenation index variability when compared with patients with normal indices (p = 0.01). Adjusting for class of congenital heart disease and duration of deep hypothermic circulatory arrest, lower postoperative cerebral tissue oxygenation index variability was associated with poor neurodevelopmental outcome (p = 0.02). Conclusions: We found reduced postoperative cerebral tissue oxygenation index variability in neonatal survivors of congenital heart disease surgery with poor neurodevelopmental outcomes. We hypothesize that reduced cerebral tissue oxygenation index variability may be a surrogate for impaired cerebral metabolic autoregulation in the immediate postoperative period. Further research is needed to investigate clinical implications of this finding and opportunities for using this measure to drive therapeutic interventions.
Keywords: aortic arch anomaly; aortic coarctation; aortic occlusion; article; brain tissue; cardiopulmonary bypass; cerebral tissue oxygenation index variability; clinical outcome; cohort analysis; comparative study; congenital heart disease; controlled study; deep hypothermic circulatory arrest; evaluation study; Fallot tetralogy; heart right ventricle double outlet; heart single ventricle; heart surgery; heart ventricle septum defect; human; hypoplastic aortic arch; hypoplastic left heart syndrome; lung vein drainage anomaly; major clinical study; mental disease; near infrared spectroscopy; near infrared spectroscopy probe; nerve cell differentiation; nervous system parameters; neurological general equipment; neuromonitoring; newborn; newborn monitoring; newborn surgery; perioperative monitoring; postoperative period; priority journal; retrospective study; surgical patient; survival; tissue oxygenation; NIRO-200

Pressure–volume loop-derived cardiac indices during dobutamine stress: a step towards understanding limitations in cardiac output in children with hypoplastic left heart syndrome - Wong, J.; Pushparajah, K.; de Vecchi, A.; Ruijsink, B.; Greil, G.F.; Hussain, T.; Razavi, R. (International Journal of Cardiology, 2017)
Background Children with a single systemic right ventricle, such as in hypoplastic left heart syndrome (HLHS), frequently experience reduced exercise capacity. Elucidating the causes could help with optimising treatment strategies. Methods Prospective data from 10 consecutive symptomatic patients with HLHS undergoing clinical cardiac magnetic resonance with catheterisation (XMR) were analysed. Mean age 8.6 years (range 3.5–11.6 years), mean time since Fontan completion 5.5 years. MR-compatible catheters were placed in the systemic right ventricle and branch pulmonary arteries to record pressures at rest, with dobutamine infusion at 10 mcg/kg/min and at 20 mcg/kg/min. Cine short-axis stacks of the ventricle were performed at each condition and used to construct pressure–volume loops. Results Compared to rest, cardiac index increased with low-dose dobutamine (p < 0.01) with no further rise at peak stress despite a further, albeit, blunted rise in heart rate (p = 0.002). A fall in stroke volume occurred (p = 0.014) despite good contractility (74% increase, p = 0.045) and a well-coupled ventriculo-arterial ratio. End-diastolic pressure and early active relaxation, markers of diastolic function, were normal at rest. However, preload fell at peak stress (p < 0.008) while pulmonary vascular resistance (PVR) was low throughout. This group of HLHS patients demonstrated a fall in SV at peak stress, coinciding with a fall in preload. Conclusions Markers of systolic and diastolic function remained normal. Failure to adequately fill the ventricle implies a ceiling of maximal flow through the Fontan circuit despite low PVR.
Keywords: dobutamine; age; article; blood flow; cardiovascular magnetic resonance; cardiovascular parameters; child; clinical article; Fontan procedure; heart catheterization; heart function; heart left ventricle filling; heart muscle contractility; heart muscle relaxation; heart output; heart preload; heart pressure volume loop; heart rate; heart right ventricle; heart stress; heart stroke volume; heart ventricle enddiastolic pressure; human; hypoplastic left heart syndrome; low drug dose; lung vascular resistance; pharmacologic stress testing; preschool child; prospective study; pulmonary artery; rest; school child

Congenital heart disease at Laos Children's Hospital: Two year experience - Hwang, I.-C.; Sisavanh, M.; Billamay, S.; Phangmanixay, S.; Oudavong, B.; Kang, J.; Kwon, B.S.; Kim, G.B.; Bae, E.J.; Noh, C.I.; Choi, J.Y. (Pediatrics International, 2017)
Background: Management of congenital heart disease (CHD) in developing countries is challenging because of limited access to health-care facilities and socioeconomic limitations. The aim of this study was to describe the recent experience with CHD at Children's Hospital, Vientiane, Laos, the only pediatric referral hospital in the country. Methods: From July 2013 to November 2015, 1009 echocardiograms were carried out in 797 individuals who visited Children's Hospital, in whom CHD was identified in 213. Demographic characteristics, echocardiography and age at first CHD diagnosis on echocardiogram were compared by residential area. Results: Among the 213 patients, the most frequent anomalies, in descending order, were ventricular septal defect, atrial septal defect, patent ductus arteriosus, and tetralogy of Fallot. Moderate or severe CHD requiring surgery or intervention was detected in 137 patients; median age at initial diagnosis was 6.0 months (IQR, 1.5–29.8). Among those with moderate or severe CHD, 89 patients were from rural areas and 48 from the capital area. The proportion of patients from rural areas older than 1 and 3 years at diagnosis was 46.1% and 32.6%, respectively. In contrast, patients from the capital area were diagnosed at a significantly earlier age: 16.7% at age >1 year and 6.2% at age >3 years (both P < 0.001 vs rural areas). Conclusions: Diagnosis of CHD requiring surgery is delayed in Laos, especially in rural areas. Better education and training of local medical staff, and greater access to medical advice are required to improve CHD care in Laos.
Keywords: age distribution; aortic coarctation; article; atrioventricular septal defect; cesarean section; child; congenital heart disease; congestive heart failure; controlled study; cyanotic heart disease; delayed diagnosis; demography; developing country; Down syndrome; echocardiography; Fallot tetralogy; female; geographic distribution; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; household income; human; hypoplastic left heart syndrome; Laos; major clinical study; male; maternal age; mortality rate; patent ductus arteriosus; prenatal care; pulmonary valve atresia; pulmonary valve stenosis; residential area; rural area; secondary care center; vaginal delivery

Psychiatric disorders in adolescents with single ventricle congenital heart disease - DeMaso, D.R.; Calderon, J.; Taylor, G.A.; Holland, J.E.; Stopp, C.; White, M.T.; Bellinger, D.C.; Rivkin, M.J.; Wypij, D.; Newburger, J.W. (Pediatrics, 2017)
BACKGROUND AND OBJECTIVES: Mental health outcomes for survivors of critical congenital heart disease (CHD) remain under-investigated. We sought to examine psychiatric disorders and psychosocial functioning in adolescents with single ventricle CHD and to explore whether patient-related risk factors predict dysfunction. METHODS: This cohort study recruited 156 adolescents with single ventricle CHD who underwent the Fontan procedure and 111 healthy referents. Participants underwent comprehensive psychiatric evaluation including a clinician-rated psychiatric interview and parent-and self-report ratings of anxiety, disruptive behavior, including attention-deficit/hyperactivity disorder (ADHD), and depressive symptoms. Risk factors for dysfunction included IQ, medical characteristics, and concurrent brain abnormalities. RESULTS: Adolescents with single ventricle CHD had higher rates of lifetime psychiatric diagnosis compared with referents (CHD: 65%, referent: 22%; P < .001). Specifically, they had higher rates of lifetime anxiety disorder and ADHD (P < .001 each). The CHD group scored lower on the primary psychosocial functioning measure, the Children's Global Assessment Scale, than referents (CHD median [interquartile range]: 62 [54-66], referent: 85 [73-90]; P < .001). The CHD group scored worse on measures of anxiety, disruptive behavior, and depressive symptoms. Genetic comorbidity did not impact most psychiatric outcomes. Risk factors for anxiety disorder, ADHD, and lower psychosocial functioning included lower birth weight, longer duration of deep hypothermic circulatory arrest, lower intellectual functioning, and male gender. CONCLUSIONS: Adolescents with single ventricle CHD display a high risk of psychiatric morbidity, particularly anxiety disorders and ADHD. Early identification of psychiatric symptoms is critical to the management of patients with CHD.
Keywords: adolescent; anxiety disorder; article; attention deficit disorder; clinical evaluation; cohort analysis; comorbidity; controlled study; deep hypothermic circulatory arrest; depression; disruptive behavior; female; Fontan procedure; heart single ventricle; human; intelligence quotient; low birth weight; major clinical study; male; mental disease; risk assessment; risk factor; scoring system; self report; social psychology; symptom

Management of Pregnancy in Patients with Complex Congenital Heart Disease: A Scientific Statement for Healthcare Professionals from the American Heart Association - Canobbio, M.M.; Warnes, C.A.; Aboulhosn, J.; Connolly, H.M.; Khanna, A.; Koos, B.J.; Mital, S.; Rose, C.; Silversides, C.; Stout, K. (Circulation, 2017)
Today, most female children born with congenital heart disease will reach childbearing age. For many women with complex congenital heart disease, carrying a pregnancy carries a moderate to high risk for both the mother and her fetus. Many such women, however, do not have access to adult congenital heart disease tertiary centers with experienced reproductive programs. Therefore, it is important that all practitioners who will be managing these women have current information not only on preconception counseling and diagnostic evaluation to determine maternal and fetal risk but also on how to manage them once they are pregnant and when to refer them to a regional center with expertise in pregnancy management.
Keywords: adrenergic receptor stimulating agent; antiarrhythmic agent; anticoagulant agent; antihypertensive agent; brain natriuretic peptide; diuretic agent; inotropic agent; purine nucleoside; thiazide diuretic agent; ablation therapy; anticoagulant therapy; arterial switch operation; article; atrial fibrillation; blood volume; cardiovascular surgery; cardioversion; clinical practice; colloid; computer assisted tomography; congenital heart disease; contraception; cyanosis; echocardiography; electrocardiogram; exercise test; female; fetus risk; first trimester pregnancy; genetic counseling; great vessels transposition; heart arrhythmia; heart atrium flutter; heart block; heart catheterization; heart failure; heart left ventricle outflow tract obstruction; heart output; heart rhythm; heart single ventricle; heart ventricle tachycardia; high risk pregnancy; human; implantable cardioverter defibrillator; intrapartum care; lifestyle; lung artery pressure; mechanical heart valve; nuclear magnetic resonance imaging; obstetric procedure; oncotic pressure; cardiac rhythm management device; paroxysmal atrial fibrillation; pregnancy; prenatal care; prenatal period; priority journal; puerperium; pulmonary hypertension; resuscitation; second trimester pregnancy; third trimester pregnancy; thorax radiography

Neurodevelopmental Outcome and Health-related Quality of Life in Children With Single-ventricle Heart Disease Before Fontan Procedure - Reich, B.; Heye, K.; Tuura, R.; Beck, I.; Wetterling, K.; Hahn, A.; Hofmann, K.; Schranz, D.; Akintürk, H.; Latal, B.; Knirsch, W. (Seminars in Thoracic and Cardiovascular Surgery, 2017)
Neurodevelopmental impairment and impaired quality of life constitute a major source of morbidity among children with complex congenital heart disease, in particular for single-ventricle (SV) morphologies. Risk factors and quality of life determining clinical and neurodevelopmental outcome at 2 years of age are examined. In a 2-center cohort study, 48 patients with SV morphology (26 hypoplastic left heart syndrome and 22 other types of univentricular heart defect) have been examined before Fontan procedure between 2010 and 2015. Patients were assessed with the Bayley Scales of Infant and Toddler Development, Third Version (Bayley-III), and the Preschool Children Quality of Life (TAPQOL) questionnaire. A total of 44 patients underwent hybrid procedure (n = 25), Norwood procedure (n = 7), or shunt or banding procedure (n = 12) as first surgery before subsequent bidirectional cavopulmonary anastomosis (n = 48). Median cognitive, language, and motor composite scores on the Bayley-III were 100 (range 65-120), 97 (68-124), and 97 (55-124), respectively. The language composite score was significantly below the norm (P = 0.025). Risk factors for poorer neurodevelopmental outcome were prolonged mechanical ventilation, longer days of hospital stay, and more reinterventions (all P < 0.05). Parents reported a good quality of life for their children. Children undergoing Fontan procedure show a favorable development and good quality of life. More complicated postoperative course and reinterventions constitute risk factors for impaired neurodevelopment. Improving postoperative management and implementing routine follow-up assessments aremeasures to further improve the neurodevelopmental outcome of this high-risk patient population.
Keywords: article; artificial ventilation; Bayley Scales of Infant Development; cavopulmonary connection; child; child development; clinical article; cohort analysis; female; Fontan procedure; heart single ventricle; hospitalization; human; hypoplastic left heart syndrome; male; nerve cell differentiation; Norwood procedure; patient assessment; postoperative period; preschool child; quality of life; quality of life assessment; questionnaire; repeat procedure; risk factor; scoring system

Long-Term Follow-Up on Health-Related Quality of Life after Mechanical Circulatory Support in Children - Fleck, T.P.K.; Dangel, G.; Bächle, F.; Benk, C.; Grohmann, J.; Kroll, J.; Siepe, M.; Höhn, R.; Kirschner, J.; Beyersdorf, F.; Stiller, B. (Pediatric Critical Care Medicine, 2017)
Objective: The objective of this study was to evaluate health-related quality of life in long-term survivors of mechanical circulatory support after acute cardiopulmonary failure. Design: Prospective follow-up study. Setting: Single-institutional in a center for congenital heart disease and pediatric cardiology. Patients: Fifty patients who underwent 58 mechanical circulatory support therapies in our institution from 2001 to 2012. Median age was 2 (0-213) months, and median supporting time was 5 (1-234) days. Indication groups: 1) extracorporeal life support in low cardiac output: 30 cases (52%); 2) extracorporeal cardiopulmonary resuscitation: 13 cases (22%); 3) extracorporeal membrane oxygenation in acute respiratory distress syndrome: four cases (7%); and 4) ventricular assist devices: 11 cases (19%). Interventions: Health-related quality of life was measured using standardized questionnaires according to the age group and completed by either parent proxies in children under 7 years old or the survivors themselves. Measurements and Main Results: Fifty percentage of the patients were discharged home, and 22 long-term survivors (44%) were studied prospectively for health-related quality of life. Median follow-up period was 4.5 (0.3-11.3) years. Median age at follow-up was 5 (0.6-29) years old. Nineteen long-term survivors filled in the health-related quality of life questionnaires and were classified into three age groups: 0-4 years (n = 7): median health-related quality of life score, 69 (59-86) points; 4-12 years (n = 7): median health-related quality of life score, 50 (48-85) points; older than 12 years (n = 5): median health-related quality of life score, 90 (80-100) points. Conclusion: Long-term survivors' health-related quality of life as reported by their parents is lower than that of healthy children. However, the self-assessed health-related quality of life of the patients older than 12 years in our group is comparable to a healthy control population.
Keywords: antithrombin III; epinephrine; fibrinogen; heparin; noradrenalin; adult respiratory distress syndrome; article; assisted circulation; atrioventricular septal defect; blood pump; cardiopulmonary insufficiency; child; child development; congestive cardiomyopathy; extracorporeal oxygenation; female; follow up; forward heart failure; great vessels transposition; heart arrest; heart right ventricle double outlet; human; hypoplastic left heart syndrome; infant; intellectual impairment; left ventricular assist device; long term survival; major clinical study; male; membrane oxygenator; motor development; pediatric cardiology; priority journal; prospective study; quality of life; questionnaire; Short Form 36; speech disorder; survivor; ventricular assist device; Deltastream DP2; Heart Excor; Heart-mate II; Paracorporeal VAD

Congenital Heart Disease in Premature Infants 25-32 Weeks’ Gestational Age - Chu, P.Y.; Li, J.S.; Kosinski, A.S.; Hornik, C.P.; Hill, K.D. (Journal of Pediatrics, 2017)
Objective To determine the birth prevalence of congenital heart defects (CHDs) across the spectrum of common defects in very/extremely premature infants and to compare mortality rates between premature infants with and without CHDs. Study design The Kids’ Inpatient Databases (2003-2012) were used to estimate the birth prevalence of CHDs (excluding patent ductus arteriosus) in very/extremely premature infants born between 25 and 32 weeks’ gestational age. Birth prevalence was compared with term infants for a subset of “severe” defects expected to be near universally diagnosed in the neonatal period. Weighted multivariable logistic regression was used to calculate aORs of mortality comparing very and extremely premature infants with vs without CHDs. Results We identified 249 011 very/extremely premature infants, including 28 806 with CHDs. The overall birth prevalence of CHDs was 116 per 1000 very/extremely premature births. Severe CHDs had significantly higher birth prevalence in very/extremely premature infants when compared with term infants (7.4 per 1000 very/premature births vs 1.5 per 1000 term births; P < .001). Very/extremely premature infants with severe CHDs had an overall 26.3% in-hospital mortality and a 7.5-fold increased adjusted odds of death compared with those without CHDs. Mortality varied widely by defect in very/extremely premature infants, ranging from 12% for interrupted aortic arch to 67% for truncus arteriosus. Conclusions Given the increased birth prevalence of severe CHDs in very/extremely premature infants, and significantly higher mortality, there is justification for intensive interventions aimed at decreasing the likelihood of premature delivery for patients where CHD is diagnosed in utero.
Keywords: aortic arch; aortic stenosis; arterial trunk; article; childhood mortality; congenital heart disease; DiGeorge syndrome; Down syndrome; Ebstein anomaly; Fallot tetralogy; female; genetic disorder; gestational age; heart atrium septum defect; heart ventricle septum defect; hospital mortality; human; infant; lung vein drainage anomaly; major clinical study; male; prematurity; priority journal; pulmonary valve atresia; pulmonary valve stenosis; term birth; tricuspid valve atresia

Effects of milk flow on the physiological and behavioural responses to feeding in an infant with hypoplastic left heart syndrome - Pados, B.F.; Thoyre, S.M.; Estrem, H.H.; Park, J.; Knafl, G.J.; Nix, B. (Cardiology in the Young, 2017)
Infants with hypoplastic left heart syndrome often experience difficulty with oral feeding, which contributes to growth failure, morbidity, and mortality. In response to feeding difficulty, clinicians often change the bottle nipple, and thus milk flow rate. Slow-flow nipples have been found to reduce the stress of feeding in other fragile infants, but no research has evaluated the responses of infants with hypoplastic left heart syndrome to alterations in milk flow. The purpose of this study was to evaluate the physiological and behavioural responses of an infant with hypoplastic left heart syndrome to bottle feeding with either a slow-flow (Dr. Brown's Preemie) or a standard-flow (Dr. Brown's Level 2) nipple. A single infant was studied for three feedings: two slow-flow and one standard-flow. Oral feeding, whether with a slow-flow or a standard-flow nipple, was distressing for this infant. During slow-flow feeding, she experienced more coughing events, whereas during standard-flow she experienced more gagging. Disengagement and compelling disorganisation were most common during feeding 3, that is slow-flow, which occurred 2 days after surgical placement of a gastrostomy tube. Clinically significant changes in heart rate, oxygen saturation, and respiratory rate were seen during all feedings. Heart rate was higher during standard-flow and respiratory rate was higher during slow-flow. Further research is needed to examine the responses of infants with hypoplastic left heart syndrome to oral feeding and to identify strategies that will support these fragile infants as they learn to feed. Future research should evaluate an even slower-flow nipple along with additional supportive feeding strategies.
Keywords: article; bottle feeding; breathing rate; case report; child behavior; child nutrition; conceptual framework; coughing; disorientation; echocardiography; feeding behavior; female; gastrointestinal symptom; heart rate; human; hypoplastic left heart syndrome; infant; oxygen saturation; stomach tube

Prognostic accuracy of antenatal neonatology consultation - Kukora, S.; Gollehon, N.; Weiner, G.; Laventhal, N. (Journal of Perinatology, 2017)
Objective:Neonatologists provide antenatal counseling to support shared decision-making for complicated pregnancies. Poor or ambiguous prognostication can lead to inappropriate treatment and parental distress. We sought to evaluate the accuracy of antenatal prognosticaltion.Study Design:A retrospective cohort was assembled from a prospectively populated database of all outpatient neonatology consultations. On the basis of the written consultation, fetuses were characterized by diagnosis groups (multiple anomalies or genetic disorders, single major anomaly and obstetric complications), assigned to five prognostic categories (I=survivable, IIA=uncertain but likely survivable, II=uncertain, IIB=uncertain but likely non-survivable, III non-survivable) and two final outcome categories (fetal demise/in-hospital neonatal death or survival to hospital discharge). When possible, status at last follow-up was recorded for those discharged from the hospital. Prognostic accuracy was assessed using unweighted, multi-level likelihood ratios (LRs).Results:The final cohort included 143 fetuses/infants distributed nearly evenly among the three diagnosis groups. Over half (64%) were assigned an uncertain prognosis, but most of these could be divided into 'likely survivable' or 'likely non-survivable' subgroups. Overall survival for the entire cohort was 62% (89/143). All but one of the fetuses assigned a non-survivable prognosis suffered fetal demise or died before hospital discharge. The neonatologist's antenatal prognosis accurately predicted the probability of survival by prognosis group (LR I=4.56, LR IIA=10.53, LR II=4.71, LR IIB=0.099, LR III=0.040). The LRs clearly differentiated between fetuses with high and low probability of survival. Eleven fetuses (7.7%) had misalignment between the predicted prognosis and outcome. Five died before discharge despite being given category I or IIA prognoses, whereas six infants with category IIB or III prognoses survived to discharge, though some of these were discharged to hospice care.Conclusions:The neonatologist's antenatal prognosis accurately predicted fetal-neonatal outcome. Infants with non-survivable or uncertain but likely poor prognoses had a very low probability of survival, whereas those with good or uncertain prognoses had a high probability of survival. There were few cases of prognostic failure with most occurring in fetuses with one major or multiple anomalies. The few cases of prognostic failure suggest a need for caution. Honest disclosure of prognostic uncertainty and shared decision-making with families utilizing their personal values is critical in the antenatal encounter.
Keywords: accuracy; adult; article; bladder obstruction; Caucasian; cause of death; central nervous system disease; cohort analysis; congenital diaphragm hernia; consultation; controlled study; data base; female; fetus; follow up; galactosialidosis; galactosialidosis type 1; genetic disorder; hospice care; hospital discharge; hospitalization; human; hypoplastic left heart syndrome; infant; labor complication; major clinical study; meningomyelocele; mucopolysaccharidosis type 7; neonatology; newborn; newborn death; oligohydramnios; outpatient; population research; prenatal care; probability; prognosis; prognostic accuracy; prospective study; resuscitation; retrospective study; survival rate

“Frontiers in Fontan failure: A summary of conference proceedings” - Hebson, C.; Book, W.; Elder, R.W.; Ford, R.; Jokhadar, M.; Kanter, K.; Kogon, B.; Kovacs, A.H.; Levit, R.D.; Lloyd, M.; Maher, K.; Reshamwala, P.; et al. (Congenital Heart Disease, 2017)
“Frontiers in Fontan Failure” was the title of a 2015 conference sponsored by Children's Healthcare of Atlanta and Emory University School of Medicine. In what is hoped to be the first of many such gatherings, speakers and attendees gathered to discuss the problem of long-term clinical deterioration in these patients. Specific focuses included properly defining the problem and then discussing different treatment strategies, both medical and surgical. The health of the liver after Fontan palliation was a particular point of emphasis, as were quality of life and future directions.
Keywords: acetylsalicylic acid; bosentan; budesonide; diuretic agent; enalapril; iloprost; sildenafil; warfarin; article; bleeding; cavopulmonary connection; clinical research; compression stocking; diastolic heart failure; drug efficacy; Fontan procedure; heart pacing; human; ischemic cardiomyopathy; kidney dysfunction; leg varicosis; liver disease; liver transplantation; medical society; nonhuman; obesity; pacemaker implantation; patient attitude; physician attitude; portal hypertension; protein losing gastroenteropathy; quality of life; resistance training; stem cell transplantation; surgical approach; surgical technique; systolic heart failure; therapy effect; thromboembolism; transitional care; treatment failure; treatment outcome; United States

Abnormalities in serum biomarkers correlate with lower cardiac index in the Fontan population - Marino, B.S.; Goldberg, D.J.; Dorfman, A.L.; King, E.; Kalkwarf, H.; Zemel, B.S.; Smith, M.; Pratt, J.; Fogel, M.A.; Shillingford, A.J.; Deal, B.J.; John, A.S.; et al. (Cardiology in the Young, 2017)
Background Fontan survivors have depressed cardiac index that worsens over time. Serum biomarker measurement is minimally invasive, rapid, widely available, and may be useful for serial monitoring. The purpose of this study was to identify biomarkers that correlate with lower cardiac index in Fontan patients. Methods and results This study was a multi-centre case series assessing the correlations between biomarkers and cardiac magnetic resonance-derived cardiac index in Fontan patients ≥6 years of age with biochemical and haematopoietic biomarkers obtained ±12 months from cardiac magnetic resonance. Medical history and biomarker values were obtained by chart review. Spearman's Rank correlation assessed associations between biomarker z-scores and cardiac index. Biomarkers with significant correlations had receiver operating characteristic curves and area under the curve estimated. In total, 97 cardiac magnetic resonances in 87 patients met inclusion criteria: median age at cardiac magnetic resonance was 15 (6-33) years. Significant correlations were found between cardiac index and total alkaline phosphatase (-0.26, p=0.04), estimated creatinine clearance (0.26, p=0.02), and mean corpuscular volume (-0.32, p<0.01). Area under the curve for the three individual biomarkers was 0.63-0.69. Area under the curve for the three-biomarker panel was 0.75. Comparison of cardiac index above and below the receiver operating characteristic curve-identified cut-off points revealed significant differences for each biomarker (p<0.01) and for the composite panel [median cardiac index for higher-risk group=2.17 L/minute/m2 versus lower-risk group=2.96 L/minute/m2, (p<0.01)]. Conclusions Higher total alkaline phosphatase and mean corpuscular volume as well as lower estimated creatinine clearance identify Fontan patients with lower cardiac index. Using biomarkers to monitor haemodynamics and organ-specific effects warrants prospective investigation.
Keywords: alkaline phosphatase; biological marker; adolescent; adult; article; cardiovascular magnetic resonance; case study; child; congenital heart disease; creatinine clearance; female; Fontan procedure; cardiac index; human; hypoplastic left heart syndrome; major clinical study; male; mean corpuscular volume; receiver operating characteristic; retrospective study; sensitivity and specificity

Differentiation of Impaired from Preserved Hemodynamics in Patients with Fontan Circulation Using Real-time Phase-velocity Cardiovascular Magnetic Resonance - Körperich, H.; Müller, K.; Barth, P.; Gieseke, J.; Haas, N.; Schulze-Neick, I.; Burchert, W.; Kececioglu, D.; Laser, K.T. (Journal of Thoracic Imaging, 2017)
Purpose: Progressive impairment of hemodynamics in patients with Fontan circulation is common, multifactorial, and associated with decreased quality of life and increased morbidity. We sought to assess hemodynamic differences between patients with preserved (preserved Fontans) and those with impaired circulation (impaired Fontans) after pulmonary vasodilation using oxygen and under forced breathing conditions. Materials and Methods: Real-time phase-contrast cardiovascular magnetic resonance was performed using non-ECG triggered echo-planar imaging (temporal resolution=24 to 28 ms) in the ascending aorta (AAo) and superior vena cava (SVC)/inferior vena cava (IVC) on room air, after 100% oxygen inhalation (4 L/min; 10 min) and on forced breathing in 29 Fontan patients (17.2±7.3 y) and in 32 controls on room air (13.4±3.7 y). The simultaneously recorded patients' respiratory cycle was divided into 4 segments (expiration, end-expiration, inspiration, and end-inspiration) to generate respiratory-dependent stroke volumes (SVs). The imaging data were matched with physiological data and analyzed with home-made software. Results: The mean SVi (AAo) was 46.1±11.1 mL/m2 in preserved Fontans versus 30.4±6.2 mL/m2 in impaired Fontans (P=0.002) and 51.1±6.9 mL/m2 in controls (P=0.107). The cutoff value for differentiation of Fontan groups was SVi (AAo, end-expiratory) of 32.1 mL/m2. After hyperoxygenation, the mean SVi (AAo) increased to 48.7±12.7 mL/m2 in preserved Fontans (P=0.045) but remained unchanged in impaired Fontans (31.1±5.8 mL/m2, P=0.665). Simultaneously, heart rates decreased from 75.2±15.9 to 70.8±16.4 bpm (preserved; P=0.000) but remained unchanged in impaired circulation (baseline: 84.1±9.8 bpm, P=0.612). Compared with physiological respiration, forced breathing increased the maximum respiratory-related cardiac index difference (ΔCImax) in preserved Fontans (SVC: 2.5-fold, P=0.000; and IVC: 1.8-fold, P=0.000) and to a lower extent in impaired Fontans (both veins, 1.5-fold; P(SVC)=0.011, P(IVC)=0.013). There was no impact on mean blood flow. Conclusions: Oxygen affected the pulmonary vascular system by vasodilation and increased SV i in preserved Fontans but had no effect on impaired Fontans. Forced breathing increased ΔCImax but did not change the mean blood flow by sole activation of the ventilatory pump. End-expiratory aortic SV i represents a valuable measure for classifying the severity of Fontan hemodynamics impairment.
Keywords: adolescent; adult; article; blood flow velocity; breathing; cardiac imaging; cardiovascular magnetic resonance; child; circulation; clinical article; controlled clinical trial; controlled study; diagnostic accuracy; diagnostic test accuracy study; echo planar imaging; Fontan procedure; cardiac index; heart rate; heart stroke volume; hemodynamics; human; hyperoxia; inferior cava vein; lung blood flow; prospective study; receiver operating characteristic; superior cava vein; vasodilatation

A comparison of the incidence of undiagnosed congenital heart disease in hospital born and home born children - Reich, J.D.; Haight, D.; Reich, Z.S. (Journal of Neonatal-Perinatal Medicine, 2017)
OBJECTIVE: To evaluate the incidence of otherwise undiagnosed congenital heart disease (CHD) in a population of children born in a hospital with routine pulse oximetry (RPO) screening compared to children born at home. METHODS: We reviewed 15 years of births at 2 hospitals for incidence of undiagnosed CHD with RPO. The Health Department reviewed the same data for out of hospital births. RESULTS: A total of 50,545 hospital births were screened and 1,274 children were born outside the hospital. There were 28 hospital-born babies diagnosed with cyanotic CHD prior to nursery discharge. Only one of these babies would not have been diagnosed without RPO. Three children were missed and there were 3 false positives. Sensitivity and positive predictive value of RPO was 25%, specificity and negative predictive value of RPO exceed 99%. The incidence of CHD requiring RPO diagnosis was roughly one birth per 50,000. Two children born at home with undiagnosed CHD were missed. One of these children presented with neonatal demise. CONCLUSION: RPO screening is still valuable in diagnosing CHD only diagnosable with RPO. However, the incidence of CHD requiring RPO to diagnose is similar to other congenital diseases which are not mandated national screening tests. In our limited experience a patient is roughly 25 times more likely to have undiagnosed CHD if they are born outside of a hospital.
Keywords: article; child; comparative study; congenital heart disease; controlled study; cyanotic heart disease; diagnostic test accuracy study; Ebstein anomaly; Fallot tetralogy; false positive result; great vessels transposition; heart single ventricle; home delivery; hospital care; human; incidence; major clinical study; newborn screening; nursery; predictive value; priority journal; pulmonary valve atresia; pulse oximetry; routine pulse oximetry; sensitivity and specificity; trisomy 21; Williams Beuren syndrome

Sirenomelia associated with hypoplastic left heart in a newborn - Turgut, H.; Ozdemir, R.; Gokce, I.; Karakurt, C.; Karadag, A. (Balkan Journal of Medical Genetics, 2017)
Sirenomelia, also known as "mermaid malformation/syndrome," is a rare, serious congenital anomaly characterized by variable degrees of fusion of the lower limbs and associated with severe malformations of vertebral, genitourinary, cardiovascular system and single umbilical artery. The first pregnancy of a 25-year-old woman resulted in one twin born by Cesarian section at 32 weeks' gestation, who was referred to our hospital with cyanosis, a congenital anomaly and respiratory distress. On physical examination, there was no urogenital region and anal fissure and gender was indeterminate. The arms were in adduction and wrist in flexion position with four fingers on the right hand and two fingers on the left hand. There was a single lower extremity with a webbed single foot and two toes consistent with sirenomelia type IV radiologically. Abdominal ultrasonography showed urogenital system agenesis and echocardiography detected hypoplastic left heart. However, the patient died 4 hours after birth. The other twin was followed for 1 week for nutrition and respiratory support and was then discharged without any problems.
Keywords: adduction; anus fissure; article; assisted ventilation; case report; cesarean section; clinical article; cyanosis; disease association; echocardiography; echography; gestational age; heart arrest; human; hypoplastic left heart syndrome; karyotype 46,XY; newborn; respiratory distress; resuscitation; sirenomelia

Neurodevelopmental Outcome of Children with Hypoplastic Left Heart Syndrome at One and Four Years of Age Comparing Hybrid and Norwood Procedure - Knirsch, W.; Liamlahi, R.; Dave, H.; Kretschmar, O.; Latal, B. (Annals of thoracic and cardiovascular surgery : official journal of the Association of Thoracic and Cardiovascular Surgeons of Asia, 2016)
Keywords: adverse event; age; child behavior; child development; cognition; comparative study; female; growth, development and aging; human; hypoplastic left heart syndrome; infant; male; motor activity; nervous system; Norwood procedure; pathophysiology; preschool child; psychology; time factor; treatment outcome

Variable Myocardial Response to Load Stresses in Infants with Single Left Ventricular Anatomy: Influence of Initial Physiology and Surgical Palliative Strategy - Horriat, N.L.; Deatsman, S.L.; Stelter, J.; Frommelt, P.C.; Hill, G.D. (Pediatric Cardiology, 2016)
Initial surgical strategies in neonates with single left ventricular (LV) anatomy vary based on adequacy of pulmonary and systemic blood flow. Differing myocardial responses to these strategies, as reflected in indices of systolic function, ventricular size, and mass have not been well defined. We sought to evaluate single LV myocardial response to varied physiology and initial palliation and determine whether the response is consistent and predictable. Infants with single LV physiology were divided based on neonatal palliation: no palliation/PA band (NO); BT shunt only (BT); or Norwood procedure (NP). Echo measures were obtained at presentation, early post-bidirectional Glenn (BDG), late post-BDG follow-up, and post-Fontan procedure. Measures included ejection fraction, LV mass indexed to height2.7 and end diastolic volume indexed to body surface area, and mass/volume ratio. The cohort included 38 children (13 NO, 13 BT, 12 NP). Ejection fraction was similar but depressed in all groups at all stages. LV mass was higher in the NP group than the BT group at early post-BDG (p = 0.03) and higher than both BT and NO groups (p < 0.01) at late post-BDG, but the difference was resolved by post-Fontan follow-up. The NP group had the most remarkable remodeling in LV size from BDG to Fontan, suggesting that volume unloading is most valuable in this subgroup. Ventricular remodeling can be identified by echocardiography in children with single LV physiology, despite variable initial surgical palliative strategies. Importantly, these initial surgical strategies do not result in significant differences after Fontan palliation during early childhood.
Keywords: article; body surface; clinical article; cohort analysis; controlled study; early intervention; echocardiography; female; follow up; Fontan procedure; Glenn shunt; heart ejection fraction; heart function; heart left ventricle enddiastolic volume; heart left ventricle mass; heart single left ventricle; heart single ventricle; heart surgery; heart ventricle remodeling; heart volume; height; human; infant; infant disease; male; newborn; Norwood procedure; palliative therapy; tricuspid valve atresia

Kabuki syndrome as a cause of non-immune fetal hydrops/ascites - Long, A.; Sinkovskaya, E.S.; Edmondson, A.C.; Zackai, E.; Schrier Vergano, S.A. (American Journal of Medical Genetics, Part A, 2016)
Kabuki syndrome (MIM 147920) is a well-described, multiple congenital anomaly syndrome characterized by growth and developmental delay, cardiac, renal, and vertebral anomalies, as well as persistent fetal finger pads and distinct facial features. Facies are characterized by long palpebral fissures with eversion of lateral third of the lower eyelid, resembling the “Kabuki make-up” theatre genre after which the syndrome is named. Kabuki syndrome is estimated to affect 1/32,000 births, with 55–80% of patients showing nonsense or frameshift mutations in the KMT2D (MLL2) gene, which encodes a histone transferase located on chromosome 12q. Additionally, owing to the heterogeneous nature of Kabuki syndrome, a smaller number of diagnosed patients have been identified with mutations or deletions in KDM6A (a component of the same transcriptional complex as KMT2D) with no mutations in KMT2D, or as those diagnosed with Kabuki syndrome and without alterations in either KMT2D or KDM6A. Diagnosis of the syndrome in newborns and infants is difficult, as the facial features are not as evident as in toddler- or childhood. There are no known “tell-tale” signs of Kabuki syndrome prenatally, and there are no reports of common, specific findings in fetuses that might suggest the diagnosis. We present here two infants who presented with prenatal hydrops/ascites, who were subsequently diagnosed with Kabuki syndrome. Although relatively non-specific, we suggest that Kabuki syndrome be added to the list of genetic syndromes that are suspected in cases of prenatal hydrops, review the molecular etiology of Kabuki syndrome, and broaden the phenotype of this well-described disorder. © 2016 Wiley Periodicals, Inc.
Keywords: amino acid substitution; amniocentesis; article; ascites; case report; cesarean section; child; female; fetal biophysical profile; fetus hydrops; gene; genetic association; genetic variability; gestational age; human; hypoplastic left heart syndrome; Kabuki makeup syndrome; KDM6A gene; KMT2D gene; lymphangiography; male; microarray analysis; missense mutation; molecular pathology; newborn; nuchal translucency measurement; nuclear magnetic resonance imaging; perinatal period; phenotype; physical examination; pleura effusion; premature fetus membrane rupture; prenatal diagnosis; preschool child; priority journal; single nucleotide polymorphism; thoracocentesis

Assessment of Risk Factors for a Sustainable “On-Table Extubation” Program in Pediatric Congenital Cardiac Surgery: 5-Year Experience - Joshi, R.K.; Aggarwal, N.; Agarwal, M.; Dinand, V.; Joshi, R. (Journal of Cardiothoracic and Vascular Anesthesia, 2016)
Objective To delineate risk factors for failure of extubation in the operating room among pediatric cardiac surgery patients. Design Prospective, observational study. Setting Single center, tertiary care, teaching hospital. Participants The study comprised 448 congenital cardiac surgery patients who were enrolled for intended extubation in the pediatric cardiac operating room over 5 years. Interventions The airways of enrolled patients were extubated in the operating room if predetermined suitability criteria were met. If the criteria were not met, patients were transferred to the intensive care unit with an endotracheal tube in situ. Patients whose airways were extubated successfully were followed up to determine specifically whether reintubation or use of noninvasive ventilation was necessary post-procedure. Measurements and Main Results The airways of 92% (412) patients were extubated in the operating room. Incidence of reintubation in the intensive care unit was 2.4%. There were 4 mortalities in the whole group. A 100% success rate for operating room extubation was achieved for patients in Risk Adjusted Congenital Heart Surgery category 1, and patients undergoing adult congenital cardiac disease surgery and redo sternotomy. The airways of 85% of patients with preoperative pulmonary hypertension were extubated in the operating room. Statistical analysis was applied to identify risk factors present in the group that made extubation in the operating room unachievable. Conclusions Extubation in the operating room was successful in a majority of patients undergoing cardiac surgery. Multivariate analysis identified weight<5 kg, age<1 year, cardiopulmonary bypass time>120 minutes, and presence of significant noncardiac structural anomalies as significant factors affecting extubation in the operating room, with an adjusted odds ratio (95% confidence interval) of 10 (2.7-37), 7.2 (2-22), 5.5 (1.7-17.7), and 3.3 (1.2-9.3), respectively. Pulmonary hypertension, redo sternotomy, higher Risk Adjusted Congenital Heart Surgery category, and aortic clamp time>60 minutes did not achieve significance in the multivariate analysis as risk factors for extubation in the operating room.
Keywords: aortopulmonary septal defect; article; child; childhood mortality; congenital heart disease; cor triatriatum; coronary artery anomaly; Down syndrome; endotracheal tube; extubation; female; follow up; Fontan procedure; Glenn shunt; heart atrium septum defect; heart right ventricle double outlet; heart right ventricle outflow tract obstruction; heart surgery; heart tumor; heart ventricle septum defect; human; infant; intensive care unit; left coronary artery; lung vein drainage anomaly; major clinical study; male; noninvasive ventilation; observational study; operating room; patent ductus arteriosus; pediatric surgery; priority journal; prospective study; pulmonary hypertension; reoperation; retreatment; sternotomy; surgical mortality; surgical patient; surgical risk; vascular ring

Early-Term Birth in Single-Ventricle Congenital Heart Disease After the Fontan Procedure: Neurodevelopmental and Psychiatric Outcomes - Calderon, J.; Stopp, C.; Wypij, D.; DeMaso, D.R.; Rivkin, M.; Newburger, J.W.; Bellinger, D.C. (Journal of Pediatrics, 2016)
Objectives To investigate the long-term impact of early-term birth (37-38 weeks’ gestation) relative to full-term birth (≥39 weeks’ gestation) on neurodevelopmental and psychiatric outcomes in adolescents with single-ventricle congenital heart disease (CHD). Study design This cross-sectional cohort study analyzed retrospective medical records from full term adolescents with single-ventricle CHD who underwent the Fontan procedure. Participants underwent neurodevelopmental and psychiatric evaluations, as well as structural brain magnetic resonance imaging. Early-term born adolescents were compared with full-term born adolescents using regression models with adjustments for family social status, birth weight, and genetic abnormality status. Medical and demographic risk factors were examined as well. Results Compared with the full-term group (n = 100), adolescents born early term (n = 33) scored significantly worse on daily-life executive functions, as measured by the Behavior Rating Inventory of Executive Function parent-report (mean scores: early term, 62.0 ± 10.9; full-term, 55.6 ± 12.2; P = .009) and self-report (P = .02) composites. Adolescents born early term were more likely than those born full term to have a lifetime attention-deficit/hyperactivity disorder (ADHD) diagnosis (early term, 55%; full term, 26%; P = .001). The early-term group also displayed greater psychiatric symptom severity, as indicated by the clinician-reported Brief Psychiatric Rating Scale (mean score: early term, 16.1 ± 8.6; full-term, 12.5 ± 8.2; P = .007). Conclusion Early-term birth is associated with greater prevalence of executive dysfunction, ADHD diagnosis, and psychiatric problems in adolescents with single-ventricle CHD. Early-term birth should be included as a potential risk factor in the algorithm for closer developmental surveillance in CHD.
Keywords: adolescent; adult; article; attention deficit disorder; behavior rating inventory of executive function; birth weight; Brief Psychiatric Rating Scale; child; child psychiatry; clinical outcome; cohort analysis; controlled study; cross-sectional study; daily life activity; demography; disease severity; executive function; female; Fontan procedure; heart single ventricle; human; major clinical study; male; medical record; mental development; neuroimaging; nuclear magnetic resonance imaging; prematurity; priority journal; race; retrospective study; risk factor; self report; sex; social status; term birth

Perioperative risk factors for impaired neurodevelopment after cardiac surgery in early infancy - Gunn, J.K.; Beca, J.; Hunt, R.W.; Goldsworthy, M.; Brizard, C.P.; Finucane, K.; Donath, S.; Shekerdemian, L.S. (Archives of Disease in Childhood, 2016)
Objective Historical cohort studies have reported adverse neurodevelopment following cardiac surgery during early infancy. Advances in surgical techniques and perioperative care have coincided with updating of neurodevelopmental assessment tools. We aimed to determine perioperative risk factors for impaired neurodevelopment at 2years following surgery for congenital heart disease (CHD) in early infancy. Design and patients We undertook a prospective longitudinal study of 153 full-term infants undergoing surgery for CHD before 2months of age. Infants were excluded if they had a genetic syndrome associated with neurodevelopmental impairment. Outcome measures Predefined perioperative parameters were recorded and infants were classified according to cardiac anatomy. At 2years, survivors were assessed using the Bayley Scales of Infant Development-III. Results At 2years, 130 children (98% of survivors) were assessed. Mean cognitive, language and motor scores were 93.4±13.6, 93.6±16.1 and 96.8±12.5 respectively (100±15 norm). Twenty (13%) died and 12 (9%) survivors had severe impairment (score <70), mostly language (8%). The lowest scores were in infants born with single ventricle physiology with obstruction to the pulmonary circulation who required a neonatal systemic-to-pulmonary artery shunt. Additional risk factors for impairment included reduced gestational age, postoperative elevation of lactate or S100B and repeat cardiac surgery. Conclusions In the modern era of infant cardiac surgery and perioperative care, children continue to demonstrate neurodevelopmental delays. The use of updated assessment tools has revealed early language dysfunction and relative sparing of motor function. Ongoing follow-up is critical in this high-risk population.
Keywords: lactic acid; protein S100B; anatomical variation; article; Bayley Scales of Infant Development; clinical assessment; cognitive defect; cohort analysis; congenital heart disease; controlled study; disease severity; female; gestational age; heart single ventricle; heart surgery; high risk infant; human; language disability; longitudinal study; lung circulation; major clinical study; male; mental disease; metabolic acidosis; newborn; newborn death; outcome assessment; perioperative period; prenatal diagnosis; priority journal; prospective study; pulmonary valve atresia; risk factor; systemic pulmonary shunt

Reduced physical exercise and health-related quality of life after Fontan palliation - Hedlund, E.R.; Lundell, B.; Villard, L.; Sjöberg, G. (Acta Paediatrica, International Journal of Paediatrics, 2016)
Aim: A growing number of patients with Fontan circulation are reaching adulthood, and there is increasing concern about their physical performance and quality of life. This study compared self-reported exercise and measured activity with quality of life in patients after Fontan palliation and healthy controls. Methods: Physical exercise during an average school week was reported by 30 Fontan circulation patients aged eight to 20 years, and 25 healthy controls, followed by accelerometer recordings over seven days. All subjects and their parents answered a questionnaire on quality of life. Results: Patients reported spending less time exercising each week than the controls (114 ± 66 minutes vs. 228 ± 147 minutes, p < 0.001). However, the overall measured activity and moderate-to-vigorous activity was similar for patients and controls. Patients reported a lower quality of life score than the controls (70.9 ± 9.9 vs. 85.7 ± 8.0, p < 0.001). Conclusion: In spite of similar measured total activity, Fontan patients reported less time engaged in regular physical exercise than healthy controls and their quality of life was lower than the controls. We speculate that promoting structured regular physical exercise could improve the quality of life of Fontan patients.
Keywords: acetylsalicylic acid; captopril; enalapril; accelerometer; adolescent; adult; age distribution; anticoagulation; article; child; circulation; clinical article; controlled clinical trial; controlled study; exercise; exercise intensity; female; Fontan procedure; human; male; cardiac rhythm management device; palliative therapy; physical performance; priority journal; quality of life; questionnaire; self report; time

Anxiety Scores in Caregivers of Children with Hypoplastic Left Heart Syndrome - Caris, E.C.; Dempster, N.; Wernovsky, G.; Butz, C.; Neely, T.; Allen, R.; Stewart, J.; Miller-Tate, H.; Fonseca, R.; Texter, K.; Nicholson, L.; Cua, C.L. (Congenital Heart Disease, 2016)
Objectives: Caring for children with congenital heart disease places significant stress on caregivers. Minimal data exist evaluating stress levels in caregivers of children with hypoplastic left heart syndrome (HLHS). The goal of this study was to obtain baseline stress scores for caregivers of children with HLHS and determine if associations exist between scores and specific caregiver factors. Study Design: A cross-sectional study using a web-based survey targeted towards caregivers of children with HLHS was performed. Baseline demographics of the caregiver and child with HLHS were obtained. Caregivers completed three validated questionnaires including the Pediatric Quality of Life Inventory (PedsQL), Parenting Stress Index- Short Form (PSI-SF) and the Pediatric Inventory for Parents (PIP). Results: Four hundred fifty-nine caregivers completed at least one questionnaire. PSI-SF total score was 80.5 ± 23.1 (> 86 = significant stress), PIP frequency total score was 119.0 ± 37.2, and PIP difficulty total score was 118.1 ± 35.7. Lower quality of life was significantly correlated with higher scores on the PSI-SF (r = −0.6), the presence of a developmental issue in the child (r = 0.3) as well as higher scores on the PIP frequency (r = −0.5) and difficulty scales (r = 0.4). Other demographic values for the caregiver and child did not significantly correlate with PSI or PIP total scores. Conclusions: Anxiety/stress scores of caregivers with children with HLHS are correlated with how well the child is perceived to be doing physically and developmentally by the caregivers. Caregivers with physical and/or developmental concerns may need added psychosocial support.
Keywords: adult; anxiety; article; caregiver burden; caregiver support; child; child development; cohort analysis; cross-sectional study; demography; developmental disorder; female; health survey; human; hypoplastic left heart syndrome; male; parental stress; Parenting Stress Index Short Form; Pediatric Inventory for Parents; Pediatric Quality of Life Inventory; priority journal; prospective study; psychosocial care; quality of life; quality of life assessment; questionnaire; stress assessment

Current therapy for hypoplastic left heart syndrome and related single ventricle lesions - Ohye, R.G.; Schranz, D.; D'Udekem, Y. (Circulation, 2016)
Universally fatal only 4 decades ago, the progress in the 3-stage palliation of hypoplastic left heart syndrome and related single right ventricular lesions has drastically improved the outlook for these patients. Although the stage II operation (hemi-Fontan or bidirectional Glenn) and stage III Fontan procedure have evolved into relatively low-risk operations, the stage I Norwood procedure remains one of the highest-risk and costliest common operations performed in congenital heart surgery. Yet, despite this fact, experienced centers now report hospital survivals of >90% for the Norwood procedure. This traditional 3-stage surgical palliation has seen several innovations in the past decade aimed at improving outcomes, particularly for the Norwood procedure. One significant change is a renewed interest in the right ventricle-to-pulmonary artery shunt as the source of pulmonary blood flow, rather than the modified Blalock-Taussig shunt for the Norwood. The multi-institutional Single Ventricle Reconstruction trial randomly assigned 555 patients to one or the other shunt, and these subjects continue to be followed closely as they now approach 10 years postrandomization. In addition to modifications to the Norwood procedure, the hybrid procedure, a combined catheter-based and surgical approach, avoids the Norwood procedure in the newborn period entirely. The initial hybrid procedure is then followed by a comprehensive stage II, which combines components of both the Norwood and the traditional stage II, and later completion of the Fontan. Proponents of this approach hope to improve not only short-term survival, but also potentially longer-term outcomes, such as neurodevelopment, as well. Regardless of the approach, traditional surgical staged palliation or the hybrid procedure, survivals have vastly improved, and large numbers of these patients are surviving not only through their Fontan in early childhood, but also into adolescence and young adulthood. As this population grows, it becomes increasingly important to understand the longer-term outcomes of these Fontan patients, not only in terms of survival, but also in terms of the burden of disease, neurodevelopmental outcomes, psychosocial development, and quality of life.
Keywords: dipeptidyl carboxypeptidase inhibitor; adolescence; adulthood; article; Blalock Taussig shunt; bradycardia; catheterization; clinical outcome; exercise; follow up; Fontan procedure; functional status; heart single ventricle; heart transplantation; human; hybrid procedure; hypoplastic left heart syndrome; kidney failure; liver failure; long term survival; lung blood flow; lung disease; nerve cell differentiation; newborn period; Norwood procedure; palliative therapy; plastic bronchitis; pregnancy; priority journal; protein losing gastroenteropathy; psychosocial development; quality of life; randomized controlled trial (topic); right ventricle to pulmonary artery conduit; short term survival; surgical approach; surgical technique; tachycardia; thromboembolism

Survival status and functional outcome of children who required prolonged intensive care after cardiac surgery - Namachivayam, S.P.; d'Udekem, Y.; Millar, J.; Cheung, M.M.; Butt, W. (Journal of Thoracic and Cardiovascular Surgery, 2016)
Background Children who require prolonged intensive care after cardiac surgery are at risk of high mortality. The long-term survival and functional outcome of these children have not been studied in detail. Methods Children who stayed in intensive care for >28 days after cardiac surgery from 1997 to 2012 were studied in a single institution. A total of 116 patients were identified; 107 (92%) were <1 year of age and 63 (54%) had univentricular physiology. Results The incidence of children requiring prolonged intensive care increased from 1.01/100 undergoing cardiac surgery in 1997 to 2000 to 2.66/100 in 2009 to 2012 (P trend = .002). This increase coincided with an increase in the number of children with hypoplastic left heart syndrome having prolonged intensive care during the same period (0.13/100 in 1997-2000 to 1.0/100 in 2009-2012; P trend = .001). Survival to pediatric intensive care unit (PICU) discharge was 74% (95% confidence interval [CI], 65-82) and 51% (95% CI, 41-59) at 3 years. Factors associated with mortality were univentricular repair (hazard ratio [HR], 2.12; 95% CI, 1.21-3.70; P = .008) and acute renal failure (HR, 3.01; 95% CI, 1.77-5.12; P < .001), but era did not influence mortality (1997-2005 vs 2006-2012; log-rank P = .66). Among PICU survivors, 3-year survival in those who did not need early reoperation was 81% (95% CI, 66-90), compared with 58% (95% CI, 42-71) in those who required early reoperation (log-rank P = .01). Among survivors, 36% had either moderate or severe disability and 13% had poor quality of life. Conclusions The incidence of children requiring prolonged intensive care after cardiac surgery has increased in our institution. Our data suggest that the long-term outcome for most of these children is poor, especially after univentricular repair.
Keywords: acute kidney failure; article; child; disability; disease severity; female; functional status; heart surgery; hospital discharge; human; hypoplastic left heart syndrome; incidence; infant; intensive care; length of stay; long term survival; major clinical study; male; mortality; outcome assessment; pediatric intensive care unit; priority journal; quality of life; reoperation; risk factor; survival time; survivor

Parents' preparedness for their infants' discharge following first-stage cardiac surgery: Development of a parental early warning tool - Gaskin, K.L.; Barron, D.J.; Daniels, A. (Cardiology in the Young, 2016)
Aim The aim of this study was to explore parental preparedness for discharge and their experiences of going home with their infant after the first-stage surgery for a functionally univentricular heart. Background Technological advances worldwide have improved outcomes for infants with a functionally univentricular heart over the last 3 decades; however, concern remains regarding mortality in the period between the first and second stages of surgery. The implementation of home monitoring programmes for this group of infants has improved this initial inter-stage survival; however, little is known about parents' experiences of going home, their preparedness for discharge, and parents' recognition of deterioration in their fragile infant. Method This study was conducted in 2011-2013; eight sets of parents were consulted in the research planning stage in September, 2011, and 22 parents with children aged 0-2 years responded to an online survey during November, 2012-March, 2013. Description of categorical data and deductive thematic analysis of the open-ended questions were undertaken. Results Not all parents were taught signs of deterioration or given written information specific to their baby. The following three themes emerged from the qualitative data: mixed emotions about going home, knowledge and preparedness, and support systems. Conclusions Parents are not adequately prepared for discharge and are not well equipped to recognise deterioration in their child. There is a role for greater parental education through development of an early warning tool to address the gap in parents' understanding of signs of deterioration, enabling appropriate contact and earlier management by clinicians.
Keywords: adult; aged; article; clinical assessment tool; clinical practice; Congenital Heart Assessment Tool; deductive thematic analysis; emotion; fear; female; first stage cardiac surgery; general aspects of disease; health education; heart single ventricle; heart surgery; home monitoring; hospital discharge; human; infant; male; medical information; middle aged; mixed emotion; online analysis; parental attitude; parental education; parental preparedness; qualitative analysis; signs of deterioration; social support; thematic analysis; treatment outcome; young adult

The Society of Thoracic Surgeons Congenital Heart Surgery Database: 2016 Update on Research - Jacobs, M.L.; Jacobs, J.P.; Pasquali, S.K.; Hill, K.D.; Hornik, C.; O'Brien, S.M.; Shahian, D.M.; Habib, R.H.; Edwards, F.H. (Annals of Thoracic Surgery, 2016)
The Society of Thoracic Surgeons Congenital Heart Surgery Database (STS CHSD) is the largest congenital and pediatric cardiac surgical clinical data registry in the world. With more than 400,000 total operations from nearly all centers performing pediatric and congenital heart operations in North America, the STS CHSD is an unparalleled platform for clinical investigation, outcomes research, and quality improvement activities in this subspecialty. In 2015, several major original publications reported analyses of data in the CHSD pertaining to specific diagnostic and procedural groups, age-defined cohorts, or the entire population of patients in the database. Additional publications reported the most recent development, evaluation, and application of metrics for quality measurement and reporting of pediatric and congenital heart operation outcomes. This use of the STS CHSD for outcomes research and for quality measurement continues to expand as database participation and the available wealth of data in it continue to grow. This article reviews outcomes research and quality improvement articles published in 2015 based on STS CHSD data.
Keywords: article; clinical outcome; congenital heart disease; data base; heart surgery; heterotaxy syndrome; human; hypoplastic left heart syndrome; lung vein drainage anomaly; medical research; medical society; mortality risk; outcomes research; palliative therapy; prenatal diagnosis; priority journal; publication; surgical mortality; thoracic surgeon; total quality management; Williams Beuren syndrome

Cardiopulmonary exercise test among children with congenital heart diseases: a multicenter study - Gavotto, A.; Amedro, P.; Guillaumont, S.; Vincenti, M.; De La Villeon, G.; Soulatges, C.; Bredy, C.; Matecki, S. (Archives of Cardiovascular Diseases Supplements, 2016)
Keywords: anaerobic threshold; article; cardiopulmonary exercise test; child; congenital heart disease; controlled study; follow up; heart left ventricle ejection fraction; heart left ventricle outflow tract obstruction; heart rehabilitation; heart right ventricle; heart right ventricle outflow tract; heart single ventricle; heart valve regurgitation; human; lung function test; major clinical study; multicenter study (topic); oxygen consumption; priority journal; quality of life; systolic blood pressure; tertiary care center

Endothelial Function and Arterial Stiffness Relate to Functional Outcomes in Adolescent and Young Adult Fontan Survivors - Goldstein, B.H.; Urbina, E.M.; Khoury, P.R.; Gao, Z.; Amos, M.A.; Mays, W.A.; Redington, A.N.; Marino, B.S. (Journal of the American Heart Association, 2016)
Background: Fontan survivors demonstrate diminished vascular function and functional outcomes, but the relationships between these measures have not been established. Methods and Results: We performed a cross-sectional study of 60 Fontan survivors (52% male) with a mean age of 13.9±4.1 years and mean Fontan duration of 9.9±4.2 years. Multimodality assessment of endothelial function (reactive hyperemia index and flow-mediated dilation) and arterial stiffness (augmentation index and baseline pulse amplitude) was performed with peripheral arterial tonometry and brachial flow-mediated dilation. Aerobic capacity was determined using cardiopulmonary exercise testing; mean peak and percentage of predicted oxygen consumption (VO2) were 27.8±7.6 mL/kg per minute and 71.0±21.2%, respectively. Quality of life and physical activity were assessed using the Pediatric Quality of Life Inventory (PedsQL) and the Physical Activity Questionnaire. Vascular measures served as predictor variables, whereas functional measures served as outcome variables. In all cases, worse vascular measures were associated with worse functional measures. Flow-mediated dilation-derived reactive hyperemia index (P<0.05) was positively associated with VO2 at anaerobic threshold. Peripheral arterial tonometry-derived baseline pulse amplitude (P<0.05) was negatively associated with the ratio of minute ventilation to carbon dioxide at anaerobic threshold. Flow-mediated dilation-derived reactive hyperemia index and peripheral arterial tonometry-derived augmentation index (P<0.05) were positively and negatively associated, respectively, with peak VO2. Maximum flow-mediated dilation (P<0.05) was positively associated with Physical Activity Questionnaire score. Peripheral arterial tonometry-derived augmentation index and baseline pulse amplitude (P<0.05) were negatively associated with parent-reported PedsQL total and physical heath summary scores. Conclusions: Increased arterial stiffness and decreased endothelial function are associated with lower aerobic capacity, physical activity, and quality of life in adolescent and young adult Fontan survivors. Understanding the cause-effect relationship between vascular function and functional outcomes is an important next step.
Keywords: carbon dioxide; adolescent; adult; aerobic capacity; age distribution; amplitude modulation; anaerobic threshold; arterial stiffness; article; augmentation index; brachial artery; cardiopulmonary exercise test; cardiovascular function; controlled study; cross-sectional study; female; flow-mediated dilation test; Fontan procedure; functional assessment; human; hyperemia; lung minute volume; major clinical study; male; operation duration; outcome assessment; outcome variable; oxygen consumption; Pediatric Quality of Life Inventory; peripheral arterial tonometry; Physical Activity Questionnaire; predictor variable; priority journal; quality of life assessment; questionnaire; scoring system; sex ratio; survivor; vascular endothelium; young adult

Rbfox2 function in RNA metabolism is impaired in hypoplastic left heart syndrome patient hearts - Verma, S.K.; Deshmukh, V.; Nutter, C.A.; Jaworski, E.; Jin, W.; Wadhwa, L.; Abata, J.; Ricci, M.; Lincoln, J.; Martin, J.F.; Yeo, G.W.; Kuyumcu-Martinez, M.N. (Scientific reports, 2016)
Hypoplastic left heart syndrome (HLHS) is a fatal congenital heart disease in which the left side of the heart is underdeveloped, impairing the systemic circulation. Underdeveloped left ventricle exerts biomechanical stress on the right ventricle that can progress into heart failure. Genome-wide transcriptome changes have been identified at early stages in the right ventricle (RV) of infants with HLHS, although the molecular mechanisms remain unknown. Here, we demonstrate that the RNA binding protein Rbfox2, which is mutated in HLHS patients, is a contributor to transcriptome changes in HLHS patient RVs. Our results indicate that majority of transcripts differentially expressed in HLHS patient hearts have validated Rbfox2 binding sites. We show that Rbfox2 regulates mRNA levels of targets with 3'UTR binding sites contributing to aberrant gene expression in HLHS patients. Strikingly, the Rbfox2 nonsense mutation identified in HLHS patients truncates the protein, impairs its subcellular distribution and adversely affects its function in RNA metabolism. Overall, our findings uncover a novel role for Rbfox2 in controlling transcriptome in HLHS.
Keywords: messenger RNA; RBFOX2 protein, human; repressor protein; RNA splicing factor; alternative RNA splicing; genetics; human; hypoplastic left heart syndrome; metabolism; newborn; pathology; stop codon

Infective endocarditis prophylaxis: Current practice trend among paediatric cardiologists: Are we following the 2007 guidelines? - Naik, R.J.; Patel, N.R.; Wang, M.; Shah, N.C. (Cardiology in the Young, 2016)
Background In 2007, the American Heart Association modified the infective endocarditis prophylaxis guidelines by limiting the use of antibiotics in patients with cardiac conditions associated with the highest risk of adverse outcomes after infective endocarditis. Our objective was to evaluate current practice for infective endocarditis prophylaxis among paediatric cardiologists. Methods A web-based survey focussing on current practice, describing the use of antibiotics for infective endocarditis prophylaxis in various congenital and acquired heart diseases, was distributed via e-mail to paediatric cardiologists. The survey was kept anonymous and was distributed twice. Results Data from 253 participants were analysed. Most paediatric cardiologists discontinued infective endocarditis prophylaxis in patients with simple lesions such as small ventricular septal defect, patent ductus arteriosus, and bicuspid aortic valve without stenosis or regurgitation; however, significant disagreement persists in prescribing infective endocarditis prophylaxis in certain conditions such as rheumatic heart disease, Fontan palliation without fenestration, and the Ross procedure. Use of antibiotic prophylaxis in certain selected conditions for which infective endocarditis prophylaxis has been indicated as per the current guidelines varies from 44 to 83%. Only 44% follow the current guidelines exclusively, and 34% regularly discuss the importance of oral hygiene with their patients at risk for infective endocarditis. Conclusion Significant heterogeneity still persists in recommending infective endocarditis prophylaxis for several cardiac lesions among paediatric cardiologists. More than half of the participants (56%) do not follow the current guidelines exclusively in their practice. Counselling for optimal oral health in patients at risk for infective endocarditis needs to be optimised in the current practice.
Keywords: antibiotic prophylaxis; aortic regurgitation; article; bacterial endocarditis; bicuspid aortic valve; cardiologist; controlled study; doctor patient relationship; Fontan procedure; health survey; heart ventricle septum defect; human; patent ductus arteriosus; patient care; patient counseling; practice guideline; rheumatic heart disease; risk factor; Ross procedure

Increasing cumulative exposure to volatile anesthetic agents is associated with poorer neurodevelopmental outcomes in children with hypoplastic left heart syndrome - Diaz, L.K.; Gaynor, J.W.; Koh, S.J.; Ittenbach, R.F.; Gerdes, M.; Bernbaum, J.C.; Zackai, E.H.; Clancy, R.R.; Rehman, M.A.; Pennington, J.W.; Burnham, N.; Spray, T.L.; et al. (Journal of Thoracic and Cardiovascular Surgery, 2016)
Objectives Despite improved survival in children with hypoplastic left heart syndrome (HLHS), significant concern persists regarding their neurodevelopmental (ND) outcomes. Previous studies have identified patient factors, such as prematurity and genetic syndromes, to be associated with worse ND outcomes. However, no consistent relationships have been identified among modifiable management factors, including cardiopulmonary bypass strategies, and ND outcomes after cardiac surgery in infancy. Studies in immature animals, including primates, have demonstrated neurodegeneration and apoptosis in the brain after certain levels and extended durations of anesthetic exposure. Retrospective human studies have also suggested relationships between adverse ND effects and anesthetic exposure. Methods Cumulative minimum alveolar concentration hours (MAC-hrs) of exposure to volatile anesthetic agents (VAA) (desflurane, halothane, isoflurane, and sevoflurane) were collected from an anesthetic database and medical record review for 96 patients with HLHS or variants. ND testing was performed between ages 4 and 5 years, including full-scale IQ, verbal IQ, performance IQ, and processing speed. Four generalized linear modes were hypothesized a priori and tested using a Gaussian (normal) distribution with an identity link. Results Cumulative VAA exposure ranged from 0 to 35.3 MAC-hrs (median 7.5 hours). Using specified covariates identified previously as significant predictors of ND outcomes, statistically significant relationships were identified between total MAC-hrs exposure and worse full-scale IQ and verbal IQ scores (P's < .05) alone and after adjusting for relevant covariates. Conclusions Increased cumulative MAC-hrs exposure to VAA is associated with worse ND outcomes in certain domains in children with HLHS and variants.
Keywords: apolipoprotein E; desflurane; halothane; inhalation anesthetic agent; isoflurane; sevoflurane; aortic arch surgery; article; child; deep hypothermic circulatory arrest; extracorporeal oxygenation; female; heart surgery; human; hypoplastic left heart syndrome; infant; intelligence quotient; left ventricular assist device; major clinical study; male; medical record review; mental disease; minimum lung alveolus concentration; nerve degeneration; priority journal; velocity

Acute ischemic stroke in a child due to basilar artery occlusion treated successfully with a stent retriever - Savastano, L.; Gemmete, J.J.; Pandey, A.S.; Roark, C.; Chaudhary, N. (Journal of NeuroInterventional Surgery, 2016)
Ischemic strokes in childhood are rare. Thrombolytic therapy with intravenous (IV) tissue plasminogen activator (tPA) has been the main intervention for the management of pediatric stroke patients, but safety data are lacking and efficacy has been questioned. Recently, successful endovascular treatments for acute ischemic stroke in children have been reported with increasing frequency, suggesting that mechanical thrombectomy can be a safe and effective treatment. We present the case of a 22-month-old child with acute ischemic stroke due to basilar artery occlusion that was successfully treated with a stent retriever.
Keywords: acetylsalicylic acid; biotinidase; nicardipine; warfarin; artery puncture; article; ataxia; basilar artery obstruction; biotinidase deficiency; brain circulus arteriosus; brain infarction; brain ischemia; case report; child; computer assisted tomography; echocardiography; female; follow up; Fontan procedure; gait disorder; guiding catheter; heart atrium septum defect; heart ventricle septum defect; human; intracardiac thrombosis; lung artery banding; magnetic resonance angiography; medical history; mental disease; mesencephalon; microcatheter; muscle tone; nuclear magnetic resonance imaging; physical examination; pons; postoperative period; priority journal; school child; stent retriever; thalamus; tricuspid valve atresia; unsteadiness; vertebral arteriography; Cello; Rebar; Solitaire

Impact of Surgical Complexity on Health-Related Quality of Life in Congenital Heart Disease Surgical Survivors - O'Connor, A.M.; Wray, J.; Tomlinson, R.S.; Cassedy, A.; Jacobs, J.P.; Jenkins, K.J.; Brown, K.L.; Franklin, R.C.; Mahony, L.; Mussatto, K.; Newburger, J.W.; Wernovsky, G.; et al. (Journal of the American Heart Association, 2016)
BACKGROUND: Surgical complexity and related morbidities may affect long-term patient quality of life (QOL). Aristotle Basic Complexity (ABC) score and Risk Adjustment in Congenital Heart Surgery (RACHS-1) category stratify the complexity of pediatric cardiac operations. The purpose of this study was to examine the relationship between surgical complexity and QOL and to investigate other demographic and clinical variables that might explain variation in QOL in pediatric cardiac surgical survivors. METHODS AND RESULTS: Pediatric Cardiac Quality of Life (PCQLI) study participants who had undergone cardiac surgery were included. The PCQLI database provided sample characteristics and QOL scores. Surgical complexity was defined by the highest ABC raw score or RACHS-1 category. Relationships among surgical complexity and demographic, clinical, and QOL variables were assessed using ordinary least squares regression. A total of 1416 patient-parent pairs were included. Although higher ABC scores and RACHS-1 categories were associated with lower QOL scores (P<0.005), correlation with QOL scores was poor to fair (r=-0.10 to -0.29) for all groups. Ordinary least squares regression showed weak association with R(2)=0.06 to R(2)=0.28. After accounting for single-ventricle anatomy, number of doctor visits, and time since last hospitalization, surgical complexity scores added no additional explanation to the variance in QOL scores. CONCLUSIONS: ABC scores and RACHS-1 categories are useful tools for morbidity and mortality predictions prior to cardiac surgery and quality of care initiatives but are minimally helpful in predicting a child's or adolescent's long-term QOL scores. Further studies are warranted to determine other predictors of QOL variation.
Keywords: adolescent; child; congenital heart malformation; factual database; female; health status; heart surgery; human; male; quality of life; survivor; therapy; United Kingdom; United States

Diagnosis of occult diastolic dysfunction late after the Fontan procedure using a rapid volume expansion technique - Averin, K.; Hirsch, R.; Seckeler, M.D.; Whiteside, W.; Beekman, R.H.; Goldstein, B.H. (Heart, 2016)
Objectives Diastolic dysfunction (DD), a key driver of long-term Fontan outcomes, may be concealed during standard haemodynamic evaluation. We sought to identify Fontan patients with occult DD using 'ventricular stress testing' with rapid volume expansion (RVE). Methods Cardiac catheterisation with RVE was performed routinely in Fontan patients between 11/2012 and 4/2015. Baseline and post-stress haemodynamic data were compared using t test, Mann-Whitney U test, Ï ‡ 2 and Fisher's exact tests. A post-stress ventricular end diastolic pressure (EDP) threshold of 15 mm Hg defined occult DD. Results Forty-six Fontan patients (48% female, median age 14.1 (IQR 9.1 to 21.3) years) were included. The median Fontan duration was 10.8 (IQR 5.1 to 17.8) years and dominant left ventricular morphology was present in 63% of patients. Volume expansion increased mean Fontan pressure (15.2±2.5 vs 12.4±2.2 mm Hg, p<0.001), pulmonary capillary wedge pressure (11.3±2.6 vs 7.9±2 mm Hg, p<0.001) and EDP (12.7±3.3 vs 8.5±2.1 mm Hg, p<0.001). Sixteen patients (35%) had occult DD, demonstrating higher baseline EDP (10.3±1.9 vs 7.6±1.5 mm Hg, p<0.001) and greater increase in EDP (6.3±2.4 vs 3.1±1.4 mm Hg, p<0.001) compared with patients without DD. Higher baseline EDP, lower baseline cardiac index and longer duration of Fontan circulation were associated with higher post-stress EDP. There were no complications related to RVE. Conclusions Ventricular stress testing by RVE is feasible, safe and identifies a subgroup of Fontan patients with occult DD. Higher baseline EDP and longer duration of Fontan circulation are associated with worse diastolic function. Future work is necessary to better understand the aetiology, associations and clinical implications of occult DD in Fontan survivors.
Keywords: dipeptidyl carboxypeptidase inhibitor; diuretic agent; adolescent; adult; article; child; clinical article; cohort analysis; controlled study; diastolic dysfunction; feasibility study; female; Fontan procedure; heart catheterization; heart failure; heart failure with preserved ejection fraction; heart function test; heart hemodynamics; cardiac index; heart left ventricle; heart ventricle enddiastolic pressure; human; lung capillary pressure; male; operation duration; patient safety; priority journal; rapid volume expansion technique; school child; treatment outcome

Outcomes of Fontan conversion for failing Fontan circulation: Mid-term results - Park, H.K.; Shin, H.J.; Park, Y.H. (Interactive Cardiovascular and Thoracic Surgery, 2016)
OBJECTIVES We investigated the results of a revision of a previous Fontan connection to total cavopulmonary connection (TCPC) in patients with failing Fontan circulation. METHODS From July 1998 to April 2013, 21 patients who had failing Fontan circulation underwent revision of the previous Fontan operation to TCPC. The median age at TCPC conversion was 17.9 years (range, 4.6-38.1 years) and the median interval between initial Fontan operation and TCPC was 13.8 years (range, 2.1-25.4 years). There were 37 indications for Fontan revision in 21 patients. The indications were huge right atrium (n = 15), atrial arrhythmia (n = 8), intra-atrial thrombi (n = 6), protein-losing enteropathy (PLE) (n = 3) and more than mild atrioventricular valve regurgitation (n = 5). The previous Fontan operation was revised to extracardiac conduit replacement (n = 20) and intra-atrial lateral tunnel (n = 1). Concomitant surgery for atrial arrhythmia was performed in 8 patients. Fenestration was performed in 7 patients. The median follow-up duration was 7.1 years (range, 0.3-13.4 years). RESULTS There were no operative deaths and two late deaths occurred 7.9 and 8.1 years after operation. Actuarial 5- and 10-year survival rates were 92.3 and 83.1%, respectively. Postoperative complications included bleeding (n = 3), deep sternal infection (n = 1) and prolonged pleural effusion for more than 2 weeks (n = 5). During follow-up, atrial arrhythmia recurred in 6 patients, PLE recurred in 2 patients and pleural effusion recurred in 2 patients. All patients were classified as New York Heart Association Class I (n = 15) or Class II (n = 4). CONCLUSIONS Fontan conversion to TCPC in patients with failing Fontan circulation can be performed with low risk of morbidity and mortality. The procedure confers better quality of life and is functional for patients with failed Fontan circulation.
Keywords: adolescent; adult; article; atrioventricular valve regurgitation; cardiopulmonary bypass; cavopulmonary connection; child; clinical article; female; follow up; Fontan procedure; great vessels transposition; heart atrium arrhythmia; heart atrium enlargement; heart atrium thrombosis; heart right atrium; human; male; New York Heart Association class; outcome assessment; pleura effusion; postoperative period; priority journal; protein losing gastroenteropathy; recurrent disease; reoperation; retrospective study; survival rate; treatment failure; tricuspid valve atresia; valvular heart disease

The Impact of a Designated Cardiology Team Involving Telemedicine Home Monitoring on the Care of Children with Single-Ventricle Physiology After Norwood Palliation - Harahsheh, A.S.; Hom, L.A.; Clauss, S.B.; Cross, R.R.; Curtis, A.R.; Steury, R.D.; Mitchell, S.J.; Martin, G.R. (Pediatric Cardiology, 2016)
We evaluated the effect of an interdisciplinary single-ventricle task force (SVTF) that utilizes a family-driven, telemedicine home monitoring program on clinical outcomes of stage II admissions and its acceptance by parents and cardiologists. Study population was divided into two cohorts, one with Norwood surgery dates before the SVTF (pre-SVTF) and one interventional (post-SVTF). Post-SVTF data also included surveys of parents and cardiologists on the efficacy of the SVTF. Comparative and multivariate statistical testing was performed. Compared to the pre-SVTF group, the post-SVTF group had lower complications after stage II (18.4 vs. 34.1 %, p = 0.02), higher weight-for-age z scores at stage II (−1.5 ± 0.97 vs. −1.58 ± 1.34, p = 0.02) and were less likely to have a stage II weight-for-age z score below −2 (26.5 vs. 31.7 %, p = 0.03). A multivariate regression analysis showed providing a written red-flag action plan to parents at discharge was independently associated with higher weight at stage II (β = 0.42, p = 0.04) and higher weight-for-age z score (β = 0.48, p = 0.02). Parents’ satisfaction with SVTF (α = 0.97) was 4.34 ± 0.62; (95 % CI 4.01–4.67) and cardiologists’ acceptance (α = 0.93) was 4.1 ± 0.7 (95 % CI 3.79–4.42). Development of SVTF was associated with a reduction in complications post-stage II and improved weight status at stage II. A written red-flag action plan provided to parents at the time of Norwood discharge was associated with higher weight status at stage II. Parents and cardiologists expressed satisfaction with the utility of SVTF and encouraged expansion to cover all children with congenital heart disease.
Keywords: acute kidney failure; adult; article; assisted circulation; atrioventricular block; cardiologist; central line infection; child; child care; chylothorax; cohort analysis; comparative study; congenital heart disease; diaphragm paralysis; endocarditis; female; heart arrest; home monitoring; human; intervention study; major clinical study; male; mediastinitis; necrotizing enterocolitis; neurologic disease; Norwood procedure; outcome assessment; parent; patient satisfaction; pericardial effusion; phrenic nerve injury; pleura effusion; pneumonia; pneumothorax; postoperative complication; postoperative hemorrhage; pulmonary hypertension; pulmonary vein obstruction; recurrent laryngeal nerve injury; reoperation; respiratory failure; seizure; septicemia; sternal dehiscence; telemedicine; tracheitis; urinary tract infection; vein occlusion; vocal cord paralysis; wound infection

Posterior reversible encephalopathy syndrome after pediatric heart transplantation: Increased risk for children with preexisting Glenn/Fontan physiology - Eilers, B.; Albers, E.; Law, Y.; Mike McMullan, D.; Shaw, D.; Kemna, M. (Pediatric Transplantation, 2016)
Identification of risk factors for PRES after organ transplant can improve early detection and avoid permanent neurological injury. High calcineurin-inhibitor levels and hypertension are recognized risk factors for PRES in adult transplant recipients. Limited data exist regarding PRES after pediatric HTx, with studies limited to case reports. We performed a retrospective review of 128 pediatric HTx recipients to identify risk factors for PRES. Seven of 128 (5.5%) recipients developed PRES at a median of 10 days (5-57) after HTx. The median age of recipients with PRES was 10.0 yr (5.7-19.0), compared to 1.4 yr (0.0-19.8) for recipients without PRES (p = 0.010). Fewer than half of recipients with PRES had elevated post-transplant calcineurin-inhibitor levels (n = 3) and/or preceding severe hypertension (n = 3). Four of seven who developed PRES (57%) had pretransplant Glenn or Fontan physiology (G/F). G/F was a significant risk factor for PRES (RR 4.99, 95% CI: 1.19-21.0, p = 0.036). Two recipients (29%), both with severe PRES, had residual neurological symptoms. In summary, PRES occurred in 5.5% of pediatric HTx recipients and presented early after HTx. All recipients with PRES were > 5 yr. Patients with pretransplant G/F were at increased risk, a risks factor not previously described.
Keywords: calcineurin inhibitor; cyclosporine; methylprednisolone; tacrolimus; thymocyte antibody; adolescent; amnesia; aortic stenosis; article; brain edema; child; clinical article; congestive cardiomyopathy; controlled study; coronary artery disease; drug dose reduction; drug megadose; drug substitution; drug withdrawal; endocardial cushion defect; female; Fontan procedure; Glenn shunt; great vessels transposition; heart transplantation; heart ventricle septum defect; human; hypertension; hypoplastic left heart syndrome; language disability; male; motor dysfunction; observational study; posterior reversible encephalopathy syndrome; preschool child; pulmonary valve atresia; retrospective study; school child; seizure

Executive functioning and school performance among pediatric survivors of complex congenital heart disease - Gerstle, M.; Beebe, D.W.; Drotar, D.; Cassedy, A.; Marino, B.S. (Journal of Pediatrics, 2016)
Objective To investigate the presence and severity of real-world impairments in executive functioning - responsible for children's regulatory skills (metacognition, behavioral regulation) - and its potential impact on school performance among pediatric survivors of complex congenital heart disease (CHD). Study design Survivors of complex CHD aged 8-16 years (n = 143) and their parents/guardians from a regional CHD survivor registry participated (81% participation rate). Parents completed proxy measures of executive functioning, school competency, and school-related quality of life (QOL). Patients also completed a measure of school QOL and underwent IQ testing. Patients were categorized into 2 groups based on heart lesion complexity: 2-ventricle or single-ventricle. Results Survivors of complex CHD performed significantly worse than norms for executive functioning, IQ, school competency, and school QOL. Metacognition was more severely affected than behavioral regulation, and metacognitive deficits were more often present in older children. Even after taking into account demographic factors, disease severity, and IQ, metacognition uniquely and strongly predicted poorer school performance. In exploratory analyses, patients with single-ventricle lesions were rated as having lower school competency and school QOL, and patients with 2-ventricle lesions were rated as having poorer behavioral regulation. Conclusions Survivors of complex CHD experience greater executive functioning difficulties than healthy peers, with metacognition particularly impacted and particularly relevant for day-to-day school performance. Especially in older children, clinicians should watch for metacognitive deficits, such as problems with organization, planning, self-monitoring, and follow-through on tasks.
Keywords: academic achievement; adolescent; adverse outcome; article; child; competence; congenital heart disease; controlled study; cross-sectional study; disease severity; executive function; female; heart injury; heart single ventricle; human; intelligence quotient; learning disorder; major clinical study; male; metacognition; predictive value; prevalence; priority journal; quality of life; survivor

Assisted reproductive technology and birth defects among liveborn infants in Florida, Massachusetts, and Michigan, 2000-2010 - Boulet, S.L.; Kirby, R.S.; Reefhuis, J.; Zhang, Y.; Sunderam, S.; Cohen, B.; Bernson, D.; Copeland, G.; Bailey, M.A.; Jamieson, D.J.; Kissin, D.M.; Backus, K.; et al. (JAMA Pediatrics, 2016)
IMPORTANCE: Use of assisted reproductive technology (ART) has been associated with increased risks for birth defects. Variations in birth defect risks according to type of ART procedure have been noted, but findings are inconsistent. OBJECTIVES: To examine the prevalence of birth defects among liveborn infants conceived with and without ART and to evaluate risks associated with certain ART procedures among ART-conceived infants. DESIGN, SETTING, AND PARTICIPANTS: Used linked ART surveillance, birth certificates, and birth defects registry data for 3 states (Florida, Massachusetts, and Michigan). Methods for ascertaining birth defect cases varied by state. Resident live births during 2000 to 2010 were included, and the analysis was conducted between Feburary 2015 and August 2015. EXPOSURES: Use of ART among all live births and use of certain ART procedures among ART births. MAINOUTCOMEANDMEASURES: Prevalenceofselected chromosomal and nonchromosomal birth defects that are usually diagnosed at or immediately after birth. RESULTS: Of the 4618 076 liveborn infants between 2000 and 2010, 64861 (1.4%) were conceived using ART. Overall, the prevalence of 1 or more of the selected nonchromosomal defects was 58.59 per10000 for ART infants (n = 389) vs 47.50 per 10000 for non-ART infants (n = 22 036). The association remained significant after adjusting for maternal characteristics and year of birth (adjusted risk ratio [aRR], 1.28; 95% CI, 1.15-1.42). Similar differences were observed for singleton ART births vs their non-ART counterparts (63.69 per 10 000 [n = 218] vs 47.17 per 10 000 [n = 21 251]; aRR, 1.38; 95% CI, 1.21-1.59). Among multiple births, the prevalence of rectal and large intestinal atresia/stenosis was higher for ART births compared with non-ART births (aRR, 2.39; 95% CI, 1.38-4.12). Among ART births conceived after fresh embryo transfer, infants born to mothers with ovulation disorders had a higher prevalence of nonchromosomal birth defects (aRR, 1.53; 95% CI, 1.13-2.06) than those born to mothers without the diagnosis, and use of assisted hatching was associated with birth defects among singleton births (aRR, 1.55; 95% CI, 1.10-2.19). Multiplicity-adjusted P values for these associations were greater than.05. CONCLUSIONS AND RELEVANCE: Infants conceived after ART had a higher prevalence of certain birth defects. Assisted hatching and diagnosis of ovulation disorder were marginally associated with increased risks for nonchromosomal birth defects; however, these associations may be caused by other underlying factors.
Keywords: adult; anencephalus; anophthalmia; article; atrioventricular septal defect; cleft lip; cleft lip palate; cleft palate; congenital malformation; controlled study; diaphragm hernia; disease association; Down syndrome; embryo transfer; encephalocele; esophagus atresia; Fallot tetralogy; female; Florida; gastroschisis; great vessels transposition; human; hypoplastic left heart syndrome; infant; infant disease; infertility therapy; intestine atresia; intestine stenosis; limb deformity; live birth; major clinical study; male; Massachusetts; Michigan; microphthalmia; mother; omphalocele; ovary insufficiency; prevalence; priority journal; spinal dysraphism; tracheoesophageal fistula; trisomy 13; trisomy 18; trisomy 21

Magnetic resonance imaging catheter stress haemodynamics post-Fontan in hypoplastic left heart syndrome - Pushparajah, K.; Wong, J.K.; Bellsham-Revell, H.R.; Hussain, T.; Valverde, I.; Bell, A.; Tzifa, A.; Greil, G.; Simpson, J.M.; Kutty, S.; Razavi, R. (European Heart Journal Cardiovascular Imaging, 2016)
Aims Exercise limitation is common post-Fontan. Hybrid X-ray and magnetic resonance imaging (XMR) catheterization allows haemodynamic assessment by means of measurement of ventricular volumes and flow in major vessels with simultaneous invasive pressures.We aim to assess haemodynamic response to stress in patients with hypoplastic left heart syndrome (HLHS) post-Fontan. Methods and results Prospective study of 13 symptomatic children (NHYA 2) with HLHS post-Fontan using XMR catheterization. Three conditions were applied: baseline (Stage 1), dobutamine at 10 mg/kg/min (Stage 2), and dobutamine at 20 μg/kg/min (Stage 3). Seven consecutive patients received inhaled nitric oxide (iNO) at peak stress. Control MRI data were from normal healthy adults. In the HLHS patients, baseline mean pulmonary vascular resistance (PVR) was 1.51±0.59WU m2 and aortopulmonary collateral flow was 17.7±13.6% of systemic cardiac output. Mean right ventricular end-diastolic pressure was 6.7±2.5 mmHg which did not rise with stress. Cardiac index (CI) increased at Stage 2 in HLHS (40%) and controls (61%) but continued to increase at Stage 3 only in controls (19%) but not in HLHS. The blunted rise in CI in HLHS was due to a continuing fall in end-diastolic volume throughout stress, with no significant change in PVR or CI at peak stress in response to iNO. Conclusion Cardiac output post-Fontan in HLHS at peak stress is blunted due to a limitation in preload which is not responsive to inhaled pulmonary vasodilators in the setting of normal PVR.
Keywords: dobutamine; nitric oxide; oxygen; article; catheter; cavopulmonary connection; child; clinical article; clinical evaluation; collateral circulation; controlled study; diagnostic catheter; elevated blood pressure; female; Fontan procedure; heart catheterization; cardiac index; heart left ventricle enddiastolic volume; heart output; heart ventricle enddiastolic pressure; hemodynamic stress; hemodynamics; human; hypoplastic left heart syndrome; lung vascular resistance; male; nuclear magnetic resonance imaging; nuclear magnetic resonance scanner; oxygen saturation; priority journal; prospective study; radiation dose; 1.5T Philips Achieva; Wedge catheter

Risk Factors and Clinical Significance of Lymphopenia in Survivors of the Fontan Procedure for Single-Ventricle Congenital Cardiac Disease - Morsheimer, M.M.; Rychik, J.; Forbes, L.; Dodds, K.; Goldberg, D.J.; Sullivan, K.; Heimall, J.R. (Journal of Allergy and Clinical Immunology: In Practice, 2016)
Background: Congenital cardiac anomalies are associated with immunologic perturbations. Surgical thymectomy, thoracic duct manipulation, and protein- losing enteropathy (PLE), a condition related to stressed Fontan hemodynamics, presumably contribute to low peripheral absolute lymphocyte counts (ALCs) and quantitative immunoglobulins. Clinical significance of lymphopenia and hypogammaglobulinemia in single-ventricle survivors requires additional study. Objective: Although immunologic laboratory anomalies are common in this population, we hypothesize that clinically significant immunodeficiency requiring intervention is rarely required. Methods: A retrospective chart review of the immunologic parameters of patients enrolled in the Single Ventricle Survivorship Program (SVSP) at the Children's Hospital of Philadelphia was performed. Results: The age range of the 178 SVSP patients was 3 to 26 years, with a median of 10.8 years. Most of the SVSP patients had some degree of lymphopenia. In the non-PLE group, the range of ALCs varied from 530 to 5322 cells/μL, with 17 patients without PLE maintaining an ALC of less than 1000 cells/μL. Among those with PLE, the median ALC and the IgG level were lower (672 cells/μL and 200 mg/dL, respectively) than in those without (1610 cells/μL and 868 mg/dL, respectively). Despite lymphopenia in the majority, few were severely clinically affected: 24% had delayed clearance of cutaneous viral infections, 63% had atopy, and 1 died of EBV-associated Hodgkin lymphoma. Immunoglobulin replacement was clinically indicated for 3 patients, 1 of whom had common variable immunodeficiency. Four patients with normal splenic function were treated with daily antibiotic prophylaxis. Conclusions: Patients with repaired single-ventricle physiology often demonstrate T-cell lymphopenia and hypogammaglobulinemia. A significant portion of patients without PLE also have lymphopenia. The most common clinical manifestation was delayed clearance of cutaneous viral infections, but significant systemic opportunistic infections were not seen despite laboratory abnormalities and lack of antimicrobial prophylaxis.
Keywords: antibiotic agent; immunoglobulin; immunoglobulin G; adolescent; adult; antibiotic prophylaxis; article; asplenia; atopy; bacteremia; cellulitis; child; common variable immunodeficiency; Epstein Barr virus infection; female; Fontan procedure; heart single ventricle; Hodgkin disease; human; lymphocyte count; lymphocytopenia; major clinical study; male; molluscum contagiosum; protein losing gastroenteropathy; retrospective study; verruca vulgaris; viral clearance; viral skin disease

The use of pre-operative halo traction to minimize risk for correction of severe scoliosis in a patient with Fontan circulation: a case report and review of literature - Chan, C.Y.W.; Lim, C.Y.; Shahnaz Hasan, M.; Kwan, M.K. (European Spine Journal, 2016)
Purpose: Patients with Fontan circulation have increased cardio-respiratory risk during major spinal surgery. We report a case of severe scoliosis with a Cobb angle of 123.3° in a 16-year-old boy with Fontan circulation treated with single stage posterior segmental pedicle screw instrumentation and fusion. Methods: Case report. Results: The use pre-operative halo-ring traction for a duration of 6 weeks in this case lead to improvement in cobb angle from 123.3°, kyphotic angle 87.1° to cobb angle of 78.0°, kyphotic angle 57.2° (on bending and stress films). The operation was completed in 150 min, blood loss 1050 ml (25 ml/kg), and cell salvage of 490 ml. He was immediately extubated post correction, but monitored in ICU for a day. Total length of stay was 8 days without any perioperative morbidity or allogeneic blood transfusion. Final post-operative radiograph showed a cobb angle of 44.2°, kyphotic angle 22.8°. Follow up at 27 months showed solid union with no significant loss of correction. Conclusion: From this case experience, pre-operative halo traction is a useful surgical strategy in patients with Fontan circulation with severe kyposcoliosis to achieve adequate correction without additional osteotomies to minimize the risk of surgical correction.
Keywords: adolescent; article; bispectral index; Blalock Taussig shunt; blood transfusion; bone graft; case report; Cobb angle; computer assisted tomography; echocardiography; extubation; follow up; Fontan procedure; fracture healing; halo brace; human; intravenous anesthesia; kyphosis; length of stay; male; morbidity; operation duration; pedicle screw; preoperative care; priority journal; scoliosis; spine radiography; traction therapy

Effect of Ambrisentan on Exercise Capacity in Adult Patients after the Fontan Procedure - Cedars, A.M.; Saef, J.; Peterson, L.R.; Coggan, A.R.; Novak, E.L.; Kemp, D.; Ludbrook, P.A. (American Journal of Cardiology, 2016)
The Fontan operation is a common end point for children born with a single functional ventricle. Fontan patients typically experience physiological deterioration leading to transplant or death in their third or fourth decades of life. This deterioration is partially attributable to progressive increases in pulmonary vascular resistance (PVR) and as such endothelin receptor antagonists, which are known to decrease pulmonary vascular resistance, have been proposed as potentially beneficial in this population. We conducted a single-center, randomized, double-blind, placebo-controlled, crossover study of 12 weeks of ambrisentan therapy (10 mg per day) versus placebo to test the hypothesis that endothelin receptor antagonism will improve cardiopulmonary exercise test parameters and 36-item short form (SF-36) assessed quality of life in adult Fontan patients. Twenty-eight patients entered the trial, 19 patients completed the protocol. Ambrisentan therapy improved peak oxygen consumption by 1.7 ml/kg/min in patients who achieved a respiratory exchange ratio of >0.95 (p = 0.05) and decreased the slope of the ventilatory equivalent ratio for oxygen (-2.8, p = 0.019) in all completers. It did not change SF-36 physical function score compared with placebo (p = 0.28). Ambrisentan therapy resulted in a decrease in (-1.4 g/dl, p <0.001) with no change in liver or renal function. Therapy was generally well tolerated, with no greater rate of side effects than placebo. In conclusion, ambrisentan is well tolerated and improves exercise capacity in adult Fontan patients.
Keywords: ambrisentan; abdominal pain; adult; arthralgia; article; cardiopulmonary exercise test; clinical article; controlled study; coughing; crossover procedure; diarrhea; double blind procedure; drug antagonism; drug effect; drug efficacy; drug tolerability; drug withdrawal; dyspnea; edema; exercise; fatigue; female; Fontan procedure; human; kidney function; liver function; lung gas exchange; male; nausea; oxygen consumption; pharyngitis; postoperative period; priority journal; quality of life; randomized controlled trial; rash; rhinitis; Short Form 36; thorax pain; treatment duration; young adult

Long-Term Serial Follow-Up of Pulmonary Artery Size and Wall Shear Stress in Fontan Patients - Bossers, S.S.M.; Cibis, M.; Kapusta, L.; Potters, W.V.; Snoeren, M.M.; Wentzel, J.J.; Moelker, A.; Helbing, W.A. (Pediatric Cardiology, 2016)
Pulmonary arterial (PA) flow is abnormal after the Fontan operation and is marked by a lack of pulsatility. We assessed the effects of this abnormal flow on the size and function of the PA’s in Fontan patients in long-term serial follow-up. Twenty-three Fontan patients with serial follow-up were included. Median age was 11.1 (9.5–16.0) years at baseline and 15.5 (12.5–22.7) years at follow-up. Median follow-up duration was 4.4 (4.0–5.8) years. Flow and size of the left pulmonary artery were determined using phase-contrast MRI. From this wall shear stress (WSS), distensibility and pulsatility were determined. A group of healthy peers was included for reference. Flow and pulsatility were significantly lower in patients than in controls (p < 0.001). Mean area was comparable in patients and controls, but distensibility was significantly higher in controls (p < 0.001). Mean and peak WSS were significantly lower in Fontan patients (p < 0.001). Between baseline and follow-up, there was a significant increase in normalized flow (15.1 (14.3–19.1) to 18.7 (14.0–22.6) ml/s/m2, p = 0.023). Area, pulsatility, distensibility and WSS did not change, but there was a trend toward a lower mean WSS (p = 0.068). Multivariable regression analysis showed that flow, area and age were important predictors for WSS. WSS in Fontan patients is decreased compared to healthy controls and tends to decrease further with age. Pulsatility and distensibility are significantly lower compared to healthy controls. Pulmonary artery size, however, is not significantly different from healthy controls and long-term growth after Fontan operation is proportionate to body size.
Keywords: adolescent; artery blood flow; artery compliance; artery diameter; article; atriopulmonary connection; cardiovascular magnetic resonance; cavopulmonary connection; child; clinical article; controlled study; cross-sectional study; female; follow up; Fontan procedure; heart right ventricle double outlet; human; hypoplastic left heart syndrome; long term care; male; multicenter study (topic); pulmonary artery; pulse wave; school child; shear stress; tricuspid valve atresia

Maternal residential exposure to agricultural pesticides and birth defects in a 2003 to 2005 North Carolina birth cohort - Rappazzo, K.M.; Warren, J.L.; Meyer, R.E.; Herring, A.H.; Sanders, A.P.; Brownstein, N.C.; Luben, T.J. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2016)
Background: Birth defects are responsible for a large proportion of disability and infant mortality. Exposure to a variety of pesticides have been linked to increased risk of birth defects. Methods: We conducted a case-control study to estimate the associations between a residence-based metric of agricultural pesticide exposure and birth defects. We linked singleton live birth records for 2003 to 2005 from the North Carolina (NC) State Center for Health Statistics to data from the NC Birth Defects Monitoring Program. Included women had residence at delivery inside NC and infants with gestational ages from 20 to 44 weeks (n=304,906). Pesticide exposure was assigned using a previously constructed metric, estimating total chemical exposure (pounds of active ingredient) based on crops within 500 meters of maternal residence, specific dates of pregnancy, and chemical application dates based on the planting/harvesting dates of each crop. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals for four categories of exposure (<10th, 10-50th, 50-90th, and >90th percentiles) compared with unexposed. Models were adjusted for maternal race, age at delivery, education, marital status, and smoking status. Results: We observed elevated ORs for congenital heart defects and certain structural defects affecting the gastrointestinal, genitourinary and musculoskeletal systems (e.g., OR [95% confidence interval] [highest exposure vs. unexposed] for tracheal esophageal fistula/esophageal atresia=1.98 [0.69, 5.66], and OR for atrial septal defects: 1.70 [1.34, 2.14]). Conclusion: Our results provide some evidence of associations between residential exposure to agricultural pesticides and several birth defects phenotypes.
Keywords: pesticide; age; amnion band syndrome; anencephalus; anophthalmia; anorectal stenosis; anotia; aortic coarctation; aortic valve stenosis; arm malformation; article; atrioventricular septal defect; bile duct atresia; case control study; central nervous system malformation; choana atresia; cleft lip; cleft palate; cohort analysis; congenital cataract; congenital diaphragm hernia; congenital malformation; controlled study; disease association; Ebstein anomaly; educational status; encephalocele; environmental exposure; epispadias; esophagus atresia; Fallot tetralogy; female; gastroschisis; great vessels transposition; harvesting; heart atrium septum defect; heart ventricle septum defect; Hirschsprung disease; human; hydrocephalus; hypertrophic pylorus stenosis; hypoplastic left heart syndrome; hypospadias; infant; kidney agenesis; leg malformation; live birth; logistic regression analysis; major clinical study; male; marriage; microcephaly; microphthalmia; microtia; obstructive genitourinary defect; omphalocele; patent ductus arteriosus; pregnancy; priority journal; pulmonary valve atresia; race; residential area; smoking; spinal dysraphism; tracheal esophageal fistula; tricuspid valve atresia; trisomy 13; trisomy 18; trisomy 21; United States

Association between fetal growth, cerebral blood flow and neurodevelopmental outcome in univentricular fetuses - Hahn, E.; Szwast, A.; Cnota, J.; Levine, J.C.; Fifer, C.G.; Jaeggi, E.; Andrews, H.; Williams, I.A. (Ultrasound in obstetrics & gynecology : the official journal of the International Society of Ultrasound in Obstetrics and Gynecology, 2016)
OBJECTIVE: To investigate the association of fetal growth and cerebrovascular resistance at different periods in gestation with neurodevelopment (ND) at 14 months in the univentricular subject. METHODS: We reviewed serial prenatal ultrasound (US) examinations from 133 infants enrolled in the Pediatric Heart Network's Single Ventricle Reconstruction or Infants with Single Ventricle trials, including a subset of 82 infants in whom ND was assessed at 14 months using mental (MDI) and psychomotor (PDI) developmental indices. US examinations were assigned to one of four gestational time periods: (1) 20-23 weeks, (2) 24-29 weeks, (3) 30-33 weeks and (4) ≥ 34 weeks. Middle cerebral artery (MCA) flow velocity was measured and pulsatility index (PI), a measure of downstream resistance, was calculated. Data on fetal head circumference (HC), femur length, abdominal circumference (AC) and estimated fetal weight (EFW) were collected and their Z-scores were calculated. We evaluated the rate of change of these parameters over time within individuals, tested correlations between fetal growth and ND and assessed predictors of ND using linear regression. RESULTS: The mean prenatal HC Z-score was < 0 at each gestational-age period and became more negative later in pregnancy. There was less growth in HC from time period 3 to period 4 compared with from period 2 to 3 (Δ HC Z-score, -0.07 ± 0.1 vs 0.11 ± 0.22, P = 0.03). Though ND did not correlate with HC, HC Z-score or MCA-PI Z-score, HC growth from period 2 to period 3 correlated with MDI (r = 0.45, P = 0.047). AC Z-score in period 4 predicted MDI (β = 4.02, P = 0.04). EFW Z-score and AC Z-score in period 2 predicted PDI (β = 10.6, P = 0.04 and β = 3.29, P = 0.047, respectively). Lower MCA-PI at initial US predicted higher PDI (β = -14.7, P = 0.03). CONCLUSION: In univentricular fetuses, lower cerebrovascular resistance may be protective for ND. Decreased fetal somatic growth may predict developmental abnormalities. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: abnormalities; brain circulation; female; fetus; fetus development; fetus echography; gestational age; heart ventricle; human; male; middle cerebral artery; mental disease; pathophysiology; physiology; pregnancy; procedures; pulsatile flow; retrospective study

Does functional health status predict health-related quality of life in children after Fontan operation? - Dulfer, K.; Bossers, S.S.M.; Utens, E.M.W.J.; Duppen, N.; Kuipers, I.M.; Kapusta, L.; Van Iperen, G.; Schokking, M.; Ten Harkel, A.D.J.; Takken, T.; Helbing, W.A. (Cardiology in the Young, 2016)
Purpose It is important to identify those children with a Fontan circulation who are at risk for impaired health-related quality of life. We aimed to determine the predictive value of functional health status - medical history and present medical status - on both physical and psychosocial domains of health-related quality of life, as reported by patients themselves and their parents. Methods We carried out a prospective cross-sectional multi-centre study in Fontan patients aged between 8 and 15, who had undergone staged completion of total cavopulmonary connection according to a current technique before the age of 7 years. Functional health status was assessed as medical history - that is, age at Fontan, type of Fontan, ventricular dominance, and number of cardiac surgical procedures - and present medical status - assessed with magnetic resonance imaging, exercise testing, and rhythm assessment. Health-related quality of life was assessed with The TNO/AZL Child Questionnaire Child Form and Parent Form. Results In multivariate prediction models, several medical history variables, such as more operations post-Fontan completion, lower age at Fontan completion, and dominant right ventricle, and present medical status variables, such as smaller end-diastolic volume, a higher score for ventilatory efficiency, and the presence of sinus node dysfunction, predicted worse outcomes on several parent-reported and self-reported physical as well as psychosocial health-related quality of life domains. Conclusions Medical history and worse present medical status not only predicted worse physical parent-reported and self-reported health-related quality of life but also worse psychosocial health-related quality of life and subjective cognitive functioning. These findings will help in identifying patients who are at risk for developing impaired health-related quality of life.
Keywords: adolescent; article; child; clinical protocol; cognition; controlled study; emotionality; exercise test; female; Fontan procedure; functional status; health status; heart rhythm; human; major clinical study; male; medical literature; motor performance; nuclear magnetic resonance imaging; outcome assessment; predictive value; prospective study; quality of life; social status

Assessing ST Segment Changes and Ischemia During Exercise Stress Testing in Patients with Hypoplastic Left Heart Syndrome and Fontan Palliation - Kyle, W.B.; Denfield, S.W.; Valdes, S.O.; Penny, D.J.; Bolin, E.H.; Lopez, K.N. (Pediatric Cardiology, 2016)
While exercise stress testing (EST) is an important tool, little is known about its use for determining ischemia in patients with hypoplastic left heart syndrome (HLHS) and Fontan palliation. We sought to determine the frequency of ST segment changes during EST in HLHS patients after Fontan and examine results of further testing performed in response to ST changes. A single-center chart review of HLHS patients post-Fontan from January 1995 to December 2012 was performed. Data collected included demographics, indications for EST, resting electrocardiogram findings, EST and echocardiogram results and outcomes. ESTs were evaluated for ST segment changes concerning for ischemia. Results of additional testing performed based on concerning EST findings were collected. Twenty-seven patients underwent 64 ESTs (mean 2.4 ESTs/patient). Median age at first EST was 9.6 years (range 6.2–16.4). EST was concerning for ischemia in 13 patients (48 %) on 25 (39 %) ESTs. Based on EST results, two patients had stress sestamibi testing, two underwent coronary angiography, and one had both. No reversible perfusion defects or coronary artery obstructions were demonstrated. No patient who underwent EST has died. ST segment depression was not associated with ventricular dysfunction prior to EST or at the end of follow-up (p > 0.05). In patients with HLHS post-Fontan palliation, ST segment depression on EST is common. In patients who underwent further testing, no evidence of ischemia or coronary abnormalities was found. Additional testing may not be necessary in all patients.
Keywords: methoxy isobutyl isonitrile technetium tc 99m; metoprolol; adolescent; angiocardiography; article; Blalock Taussig shunt; cardiopulmonary exercise test; child; clinical article; echocardiography; electrocardiogram; female; fenestration; follow up; Fontan procedure; heart arrhythmia; heart catheterization; heart muscle ischemia; heart right bundle branch block; heart surgery; heart ventricle function; heart ventricle hypertrophy; heart ventricle tachycardia; Holter monitoring; human; hypoplastic left heart syndrome; male; medical record review; myocardial perfusion imaging; Norwood procedure; palliative therapy; Sano modification; school child; ST segment; ST segment depression; supraventricular tachycardia; treadmill exercise

Improving Neurodevelopmental Surveillance and Follow-up in Infants with Congenital Heart Disease - Michael, M.; Scharf, R.; Letzkus, L.; Vergales, J. (Congenital Heart Disease, 2016)
Objective: We hypothesize that neurodevelopmental surveillance of targeted patients with congenital heart disease during the admission for their cardiac surgery would improve neurodevelopmental assessment and outpatient follow-up rates. Design: All patients under 12 months of age who were operated on between October 2013 and October 2014 and were considered at risk for neurodevelopmental delay in accordance with the 2012 American Heart Association Scientific Statement were included. A protocol was implemented to increase surveillance of targeted patients during the hospitalization for their cardiac surgery. A historical control cohort was used from a 6-month period that preceded initiation of the program from July 2012 to December 2012. Univariate analysis assessed the effects of patient demographics, anatomy, postoperative course, and distance from clinic on inpatient screening and follow-up to evaluate areas for future improvement. Results: Neurodevelopmental surveillance in the post-protocol period increased from 21% to 82% (P<.001) as did compliance rates for outpatient follow-up from 38% to 52% (P<.001). Patients receiving consultation were younger (median 1.2 months range 0.3-3.1 vs. 4.0 range 1.2-5.5, P=.002), had a longer intensive care unit duration (median 8 days range 4-13 vs. 4 range 3-8, P=.044), and a longer total hospital duration (median 14 days range 8-25 vs. 8 range 6-16, P=.023). The presence of single ventricle anatomy was associated with a lower follow-up rate at 29% than those with biventricular hearts at 64% (P=.009). Distance from the clinic did not have an effect on follow-up (P=.39). Conclusion: The protocol described increased neurodevelopmental surveillance of high risk patients. Individuals that were younger and in the hospital longer were more likely to be successfully seen and comply with outpatient follow-up than those not receiving inpatient risk assessment. Patients with single ventricle anatomy may benefit from a modified follow-up schedule to improve compliance rates. Travel distance has no effect on likelihood of outpatient cardiac neurodevelopmental follow-up.
Keywords: age distribution; article; biventricular heart; congenital heart disease; congenital heart malformation; consultation; developmental disorder; developmental screening; disease surveillance; female; follow up; health care utilization; heart single ventricle; human; infant; intensive care unit; length of stay; major clinical study; male; mental disease; neurodevelopmental delay; priority journal; travel

Can a Home-based Cardiac Physical Activity Program Improve the Physical Function Quality of Life in Children with Fontan Circulation? - Jacobsen, R.M.; Ginde, S.; Mussatto, K.; Neubauer, J.; Earing, M.; Danduran, M. (Congenital Heart Disease, 2016)
Objective: Patients after Fontan operation for complex congenital heart disease (CHD) have decreased exercise capacity and report reduced health-related quality of life (HRQOL). Studies suggest hospital-based cardiac physical activity programs can improve HRQOL and exercise capacity in patients with CHD; however, these programs have variable adherence rates. The impact of a home-based cardiac physical activity program in Fontan survivors is unclear. This pilot study evaluated the safety, feasibility, and benefits of an innovative home-based physical activity program on HRQOL in Fontan patients. Methods: A total of 14 children, 8-12 years, with Fontan circulation enrolled in a 12-week moderate/high intensity home-based cardiac physical activity program, which included a home exercise routine and 3 formalized in-person exercise sessions at 0, 6, and 12 weeks. Subjects and parents completed validated questionnaires to assess HRQOL. The Shuttle Test Run was used to measure exercise capacity. A Fitbit Flex Activity Monitor was used to assess adherence to the home activity program. Results: Of the 14 patients, 57% were male and 36% had a dominant left ventricle. Overall, 93% completed the program. There were no adverse events. Parents reported significant improvement in their child's overall HRQOL (P<.01), physical function (P<.01), school function (P=.01), and psychosocial function (P<.01). Patients reported no improvement in HRQOL. Exercise capacity, measured by total shuttles and exercise time in the Shuttle Test Run and calculated VO2max, improved progressively from baseline to the 6 and 12 week follow up sessions. Monthly Fitbit data suggested adherence to the program. Conclusion: This 12-week home-based cardiac physical activity program is safe and feasible in preteen Fontan patients. Parent proxy-reported HRQOL and objective measures of exercise capacity significantly improved. A 6-month follow up session is scheduled to assess sustainability. A larger study is needed to determine the applicability and reproducibility of these findings in other age groups and forms of complex CHD.
Keywords: article; child; clinical article; clinical assessment tool; exercise intensity; feasibility study; female; Fitbit Flex Activity Monitor; follow up; Fontan procedure; functional status; health program; home care; human; male; outcome assessment; patient safety; physical activity; physical capacity; physical performance; pilot study; preschool child; priority journal; program effectiveness; quality of life; questionnaire; school child; social psychology; The Shuttle Test Run; treatment duration; venous oxygen tension

Assessment of Quality of Life in Young Patients with Single Ventricle after the Fontan Operation - Uzark, K.; Zak, V.; Shrader, P.; McCrindle, B.W.; Radojewski, E.; Varni, J.W.; Daniels, K.; Handisides, J.; Hill, K.D.; Lambert, L.M.; Margossian, R.; Pemberton, V.L.; et al. (Journal of Pediatrics, 2016)
Objectives To assess self-reported quality of life (QOL) in a large multicenter cohort of adolescent and young adults surviving Fontan. Study design Cross-sectional. The Pediatric Quality of Life Inventory (PedsQL) was administered to 408 survivors of Fontan ages 13-25 years enrolled in the Pediatric Heart Network Fontan Follow-up Study. Subjects also completed either the Child Health Questionnaire (age <19 years) or Short Form Health Survey (age ≥19 years). PedsQL data were compared with matched controls without a chronic health condition. Correlations between the measures were examined. Results Mean PedsQL scores for subjects receiving Fontan were significantly lower than those for the control group for physical and psychosocial QOL (P <.001). Overall, 45% of subjects receiving Fontan had scores in the clinically significant impaired range for physical QOL with 30% in the impaired range for psychosocial QOL. For each 1 year increase in age, the physical functioning score decreased by an average of 0.76 points (P =.004) and the emotional functioning score decreased by an average of 0.64 points (P =.03). Among subjects ≥19 years of age, the physical functioning score decreased by an average of 2 points for each year increase in age (P =.02). PedsQL scale scores were significantly correlated with conceptually related Child Health Questionnaire (P <.001) and Short Form Health Survey scores (P <.001). Conclusions Survivors of Fontan are at risk for significantly impaired QOL which may decline with advancing age. Routine assessment of QOL is essential to inform interventions to improve health outcomes. The PedsQL allowed QOL assessment from pediatrics to young adulthood. Trial registration ClinicalTrials.gov: NCT00132782.
Keywords: NCT00132782; Fontan procedure; adolescent; adult; article; Child Health Questionnaire; cohort analysis; comparative study; controlled clinical trial; controlled study; cross-sectional study; emotion; female; follow up; Fontan procedure; heart single ventricle; human; major clinical study; male; multicenter study; Pediatric Quality of Life Inventory; physical activity; physical performance; priority journal; quality of life; quality of life assessment; self report; Short Form 36; social interaction; social psychology; survival; young adult

Noncardiac Challenges in the Cardiac ICU: Feeding, Growth and Gastrointestinal Complications, Anticoagulation, and Analgesia - Hehir, D.A.; Easley, R.B.; Byrnes, J. (World Journal for Pediatric and Congenital Heart Surgery, 2016)
Outcomes following cardiac intensive care unit (CICU) admission are influenced by many factors including initial cardiac diagnosis, surgical complexity, and burden of critical illness. Additionally, the presence of noncardiac issues may have a significant impact on outcomes and the patient experience during and following an intensive care unit stay. This review focuses on three common noncardiac areas which impact outcomes and patient experience in and beyond the CICU: feeding and growth, pain and analgesia, and anticoagulation. Growth failure and feeding dysfunction are commonly encountered in infants requiring cardiac surgery and have been associated with worse surgical and developmental outcomes. Recent studies most notably in the single ventricle population have demonstrated improved weight gain and outcomes when feeding protocols are implemented. Children undergoing cardiac surgery may experience both acute and chronic pain. Emerging research is investigating the impact of sedatives and analgesics on neurodevelopmental outcomes and quality of life. Improved pain scores and standardized management of pain and withdrawal may improve the patient experience and outcomes. Effective anticoagulation is a critical component of perioperative care but may be complicated by inflammation, multiorgan dysfunction, and patient factors. Advances in monitoring of anticoagulation and emerging therapies are reviewed.
Keywords: analgesic agent; blood clotting factor; heparin; sedative agent; analgesia; anesthesia level; anticoagulation; article; blood clotting; coronary care unit; cardiac patient; chronic pain; congenital heart disease; feeding difficulty; growth disorder; heart single ventricle; heart surgery; heparin induced thrombocytopenia; human; hypoplastic left heart syndrome; inflammation; intensive care unit; multiple organ failure; outcome assessment; partial thromboplastin time; perioperative period; priority journal; quality of life; scoring system; body weight gain

Restrictive atrial septum after the Fontan procedure - Penford, G.; Quandt, D.; Stumper, O. (Cardiology in the Young, 2016)
In this study, three patients presenting with early or late postoperative Fontan complications were identified to suffer from restriction of the native atrial septum. This caused significant obstruction to pulmonary venous return and elevated systemic venous pressure. Dobutamine stress testing was used in one patient to identify this lesion. Transcatheter stenting was performed in the other two patients. Patients improved after relief of the obstruction.
Keywords: dobutamine; article; case report; child; clinical feature; disease association; female; fenestration; follow up; Fontan procedure; heart disease; heart left atrium pressure; heart right atrium pressure; heart surgery; human; hypoplastic left heart syndrome; male; medical history; patient assessment; pharmacologic stress testing; pleura effusion; postoperative complication; postoperative period; preoperative period; preschool child; protein losing gastroenteropathy; restrictive atrial septum; school child; transthoracic echocardiography; treatment response; Genesis

Quality of Life of Pediatric Patients with Long QT Syndrome - Czosek, R.J.; Kaltman, J.R.; Cassedy, A.E.; Shah, M.J.; Vetter, V.L.; Tanel, R.E.; Wernovksy, G.; Wray, J.; Marino, B.S. (American Journal of Cardiology, 2016)
Children with long QT syndrome (LQTS) live with the risk of sudden death, activity restrictions, and the need for daily medications. We sought to evaluate the quality of life (QOL), self-perception, and behavior of patients with LQTS as perceived by both patients and their parents and identify predictors of lower QOL. QOL (Pediatric QOL Inventory [PedsQL] and Pediatric Cardiac Quality of Life Inventory [PCQLI]), self-perception, and behavioral inventories were completed by patients with LQTS and their parents. Comparison of PedsQL scores was made to published data for healthy children using t tests, and PCQLI scores were compared with those of patients with differing complexity of congenital heart disease. Mixed modeling was used for multivariable analysis. Sixty-one patients with LQTS were evaluated (age 13.6 ± 3.0 years; male 49%). Compared with healthy children, the PedsQL Total, Psychosocial, and Physical Health Summary scores were significantly lower for patients with LQTS and parent proxy reports (p ≤0.001). In general, PCQLI scores of patients with LQTS and parents were similar to those of patients with tetralogy of Fallot (p ≥0.2), lower than those of patients with bicuspid aortic valve (p ≤0.02), and higher than those of patients with single ventricle (p ≤0.03). Lower patient and parent PCQLI scores were associated with internalizing problems. For parents, the presence of a cardiac device and medication side effects were additionally associated with lower PCQLI scores. In conclusion, patients with LQTS and their parents report lower QOL than normal children secondary to physical and psychosocial factors. Increasing focus on the psychological well-being of these patients is needed in an effort to improve their QOL.
Keywords: cardiac agent; adolescent; article; bicuspid aortic valve; cardiac equipment; child; congenital heart disease; Fallot tetralogy; female; heart single ventricle; human; long QT syndrome; major clinical study; male; outcome variable; priority journal; psychological well-being; quality of life; social psychology

Congenital Heart Defects and Indices of Fetal Cerebral Growth in a Nationwide Cohort of 924 422 Liveborn Infants - Matthiesen, N.B.; Henriksen, T.B.; Gaynor, J.W.; Agergaard, P.; Bach, C.C.; Hjortdal, V.E.; Østergaard, J.R. (Circulation, 2016)
Background-Neurodevelopmental disorders are the most common and distressful comorbidities associated with congenital heart defects (CHD). Head circumference at birth (HC), a proxy for prenatal cerebral growth, is an established risk factor for neurodevelopmental disorders. Methods and Results-In a nationwide cohort, we included all 924 422 liveborn Danish singletons, 1997 to 2011. CHD was present in 5519. The association between CHD and growth indices was analyzed by multivariable linear regression, adjusted for potential confounders. We report mean differences in gestational age-specific z scores in comparison with the general population. CHD was associated with lower HC z scores,-0.10 (95% confidence interval [CI],-0.13 to-0.08). Several CHD subtypes were associated with smaller HC, eg, hypoplastic left heart syndrome,-0.39 (95% CI,-0.58 to-0.21); common arterial trunk,-0.41 (95% CI,-0.74 to-0.09); and major ventricular septal defects,-0.25 (95% CI,-0.35 to-0.15). Other single-ventricle defects, transposition of the great arteries, tetralogy of Fallot, and anomalous pulmonary venous return, were also associated with smaller HC. Transposition of the great arteries was associated with smaller HC relative to birth weight,-0.26 (95% CI,-0.39 to-0.13). Major ventricular septal defects were associated with larger HC relative to birth weight. The results were consistent under various conditions, eg, when siblings of infants with CHD (n=5311) or infants with other major malformations (n=24 974) were used as the reference. Conclusions-Several subtypes of CHD were associated with smaller HC. The associations with major ventricular septal defects, common arterial trunk, and anomalous pulmonary venous return have not previously been described. Only infants with transposition of the great arteries had smaller HC relative to birth weight.
Keywords: aortic arch anomaly; aortic coarctation; aortic stenosis; arterial trunk; article; atrioventricular septal defect; brain development; cohort analysis; congenital heart malformation; disease association; Fallot tetralogy; gestational age; great vessels transposition; head circumference; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; human; hypoplastic left heart syndrome; live birth; lung vein drainage anomaly; major clinical study; mental disease; newborn; priority journal; pulmonary valve atresia; pulmonary valve stenosis; risk assessment; risk factor

Multi-institutional evaluation of the indications and radiation dose of functional cardiovascular computed tomography (CCT) imaging in congenital heart disease - Han, B.K.; Hlavacek, A.M.; Kay, W.A.; Pham, T.D.N.; Grant, K.; Garberich, R.F.; Lesser, J.R.; Raman, S.V. (International Journal of Cardiovascular Imaging, 2016)
Ventricular volumes and ejection fraction are often used in clinical decision making in patients with congenital heart disease (CHD). The referral diagnosis, radiation exposure and image quality of functional cardiac computed tomography (CT) in a relatively large cohort of patients of CHD has not been reported. This is a retrospective evaluation of functional CT studies performed in CHD patients from three institutions (1/2007–3/2013). Patient and scanner characteristics, radiation dose estimates and image quality were compared. Two hundred ninety-eight functional CT studies were evaluated. The most common referral diagnosis were tetralogy of Fallot (33 %), transposition complexes (24 %) single ventricle heart disease (15 %), and left sided obstruction (15 %). The reason for cardiac CT was presence of pacemaker (60 %), need for detailed coronary artery imaging (18 %), metallic artifact in CMR (12 %), evaluation of prosthetic valve function (4 %), and claustrophobia or BMI too large for the available MR scanner (6 %). 266 (89.3 %) scans allowed quantification of ventricular function, 25 (8.4 %) scans allowed qualitative assessment of function, and 7 (2.3 %) of the scans were non-diagnostic for functional analysis. Median DLP was 399 mGy cm (186, 614), and median effective dose was 5.5 mSv (2.6, 8.5). Radiation dose and image quality varied across institutions. Cardiac CT function imaging can be performed in patients with congenital heart disease when CMR is contraindicated or has poor image quality. Radiation dose and image quality varies across institutions.
Keywords: adolescent; adult; age distribution; article; body height; body mass; body weight; cardiac imaging; cardiovascular computer assisted tomography; cardiovascular magnetic resonance; child; claustrophobia; comparative study; computed tomography scanner; computer assisted tomography; congenital heart disease; controlled study; dosimetry; Fallot tetralogy; female; heart left ventricle function; heart left ventricle outflow tract obstruction; heart valve prosthesis; heart ventricle failure; human; image processing; image quality; major clinical study; male; cardiac rhythm management device; patient referral; radiation dose; retrospective study; risk assessment; sex difference; supraventricular tachycardia; Somatom Definition; Somatom Definition Flash; Somatom Sensation 64

Gastrostomy Tube Feeding after Neonatal Complex Cardiac Surgery Identifies the Need for Early Developmental Intervention - Ricci, M.F.; Alton, G.Y.; Ross, D.B.; Dicken, B.J.; Moddemann, D.M.; Robertson, C.M.T.; Rebeyka, I.M.; Garcia Guerra, G.; Atallah, J.; Dinu, I.A.; Blakley, P.; Bodani, J.; et al. (Journal of Pediatrics, 2016)
Objective To compare the proportion of developmental delay in early complex cardiac surgery (CCS) survivors with and without gastrostomy tube feeding (GTF). To explore acute care predictors of GTF that might help improve care in CCS survivors. Study group This comparison study of 2 groups within an inception cohort included 334 CCS survivors after cardiopulmonary bypass at ≤6 weeks of age (2005-2012) who did not require extracorporeal membrane oxygenation or heart transplantation. Children were assessed at 21 ± 3 months with the Bayley Scales of Infant and Toddler Development-Third Edition and the Adaptive Behavior Assessment System-Second Edition: general adaptive composite score. Delay was determined by scores >2 SD below mean. The χ2 test compared groups. Predictors of GTF were analyzed using multiple logistic regression analysis, results expressed as OR with 95% CI. Results Of the survivors, 67/334 (20%) had GTF any time before the 21-month assessment. Developmental delays in children with GTF were cognitive in 16 (24%), motor in 18 (27%), language in 24 (36%) vs without GTF in 7 (3%), 8 (3%), and 32 (12%), respectively (P <.001). Gastrostomy group had almost 8 times the number of children delayed on the general adaptive composite score. Independent OR for GTF are presence of a chromosomal abnormality, OR 4.6 (95% CI 1.8, 12.0) (P =.002), single ventricle anatomy, OR 3.4 (95% CI 1.7, 6.8) (P <.001), total postoperative days of open sternum, OR 1.15 (95% CI 1.1, 1.3) (P =.031), and total number of hospital days at CCS, OR 1.03 (95% CI 1.1, 1.04) (P =.002). Conclusions GTF identifies CCS survivors at risk for delay, who would benefit from early developmental intervention. The described mostly nonmodifiable predictors may guide counseling of these children's families.
Keywords: anatomy; article; Bayley Scales of Infant Development; cardiopulmonary bypass; child; chromosome aberration; cognitive defect; developmental disorder; early intervention; enteric feeding; extracorporeal oxygenation; female; heart single ventricle; heart surgery; heart transplantation; human; intestine malrotation; language delay; length of stay; lung vein drainage anomaly; major clinical study; male; motor dysfunction; postoperative period; prenatal diagnosis; priority journal; stomach tube; survivor

The Effect of Noncardiac and Genetic Abnormalities on Outcomes Following Neonatal Congenital Heart Surgery - Alsoufi, B.; Gillespie, S.; Mahle, W.T.; Deshpande, S.; Kogon, B.; Maher, K.; Kanter, K. (Seminars in Thoracic and Cardiovascular Surgery, 2016)
Significant noncardiac and genetic abnormalities (NC and GA) are common in neonates with congenital heart defects. We sought to examine current-era effect of those abnormalities on early and late outcomes following cardiac surgery. The method from 2002-2012, 1538 neonates underwent repair (n = 860, 56%) or palliation (n = 678, 44%) of congenital heart defects. Regression models examined the effect of NC and GA on operative results, resource utilization, and late outcomes. Neonates with NC and GA (n = 312, 20%) had higher incidence of prematurity (21% vs 13%; P < 0.001) and weight ≤2.5 kg (24% vs 12%; P < 0.001) than neonates without NC and GA (n = 1226, 80%). Although the incidence of single ventricle was comparable (34% vs 31%; P = 0.37), neonates with NC and GA underwent more palliation (52% vs 42%; P = 0.001) and subsequently had higher percentage of STAT mortality categories (Society of Thoracic Surgeons (STS) and the European Association for Cardio-thoracic Surgery (EACTS) Congenital Heart Surgery Mortality Categories) 4 and 5 procedures (78% vs 66%; P < 0.001). Adjusted logistic regression models that included disparate patient and operative variables showed that the presence of NC and GA was associated with increased unplanned reoperation (odds ratio = 1.7; 95% CI: 1.1-2.7; P = 0.03) and hospital mortality (odds ratio = 2.2; 95% CI: 1.3-3.6; P = 0.002). Adjusted linear regression models showed significant association between NC and GA and increased postoperative mechanical ventilation duration, intensive care unit, and hospital stays (P < 0.001 each). Adjusted hazard analysis showed that the presence of NC and GA was associated with diminished late survival (hazard ratio = 2.4; 95% CI: 1.9-3.1; P < 0.001) and that was evident in all subgroups of patients (P < 0.001 each). Conclusion is neonates with NC and GA commonly have associated risk factors for morbidity and mortality such as prematurity and low weight. After adjusting for those factors, the presence of NC and GA continues to have significant association with increased unplanned reoperation, hospital mortality, and resource utilization after palliative and corrective cardiac surgery. Importantly, the hazard of death in those patients continues beyond the perioperative period for at least 1 year. Our findings show that the presence of NC and GA should be emphasized during parent counseling and decision making; and underscore the need to explore strategies to improve outcomes for this high-risk population that must address perioperative care, outpatient surveillance, and management.
Keywords: acrocephalosyndactyly; Alagille syndrome; article; artificial ventilation; body weight; cardiopulmonary bypass; cat cry syndrome; CHILD syndrome; cohort analysis; controlled study; Dandy Walker syndrome; DiGeorge syndrome; Down syndrome; extracorporeal oxygenation; female; genetic disorder; Goldenhar syndrome; happy puppet syndrome; hazard assessment; health care utilization; heart single ventricle; heart surgery; heterotaxy syndrome; Holt Oram syndrome; hospital mortality; hospitalization; human; incidence; intensive care unit; Jacobsen syndrome; karyotype 47,XYY; Klinefelter syndrome; Klippel Feil syndrome; logistic regression analysis; major clinical study; male; Mowat Wilson syndrome; newborn; Noonan syndrome; palliative therapy; phenylketonuria; Pierre Robin syndrome; prematurity; reoperation; sickle cell anemia; survival; syndrome CHARGE; trisomy 13; trisomy 18; Turner syndrome; VACTREL syndrome

Takotsubo cardiomyopathy in a 22-year-old single-ventricle patient - Derk, G.R.; Aboulhosn, J.; Reardon, L.C. (Texas Heart Institute Journal, 2016)
We report a highly unusual case of a 22-year-old woman with single-ventricle anatomy and a history of Fontan palliation who developed takotsubo cardiomyopathy. To our knowledge, takotsubo cardiomyopathy has not previously been described in a patient with single-ventricle anatomy, or more generally in any patient with congenital heart disease. The patient presented at our clinic for urgent examination after a 2-day history of chest pain that had begun upon the death of her dog. Invasive evaluation was refused by the patient; instead, she underwent electrocardiogram-gated coronary computed tomographic angiography, to rule out obstructive coronary disease. A physician who suspects takotsubo cardiomyopathy in a patient should look for new-onset chest pain and dyspnea coupled with these features: immediate onset of segmental akinesia in the midventricular or apical aspects of the heart, elevation of brain natriuretic peptide level 12 to 24 hours after onset of akinesia, elevation of troponin level 24 to 48 hours after onset, and disappearance of the segmental akinesia a few days after onset.
Keywords: acetylsalicylic acid; benzodiazepine; brain natriuretic peptide; clonazepam; ibuprofen; metoprolol; troponin; adult; akinesia; article; case report; computed tomographic angiography; dyspnea; echocardiography; electrocardiography; female; heart single ventricle; human; hyperventilation; takotsubo cardiomyopathy; thorax pain; young adult

Pulmonary artery branch stent implantation in congenital heart disease: A 10-year multicenter experience - Peirone, A.; Contreras, A.; Cabrera, M.; Guadagnoli, A.F.; Gentiletti, A.; Schroh, A.; Laghezza, L.; Juaneda, I.; Díaz, J.; Kreutzer, C. (Revista Argentina de Cardiologia, 2016)
Background: Stent implant is considered the treatment of choice for most cases of congenital or postoperative pulmonary artery branch stenosis in patients with congenital heart defects. However, there are still doubts on the clinical effectiveness and the incidence of complications of this technique that need to be elucidated. Methods: This multicenter study has a descriptive, observational and retrospective design. The procedures were performed between January 2005 and April 2015. Twenty-five patients with pulmonary artery branch stenosis underwent stent implant and were followed-up both clinically and by different imaging tests. Persistent clinical and/or anatomic improvement defined clinical effectiveness. Results: Average age was 9.48 years (2 months-34 years), mean weight was 27.54 kg (3-104 kg) and 44% were women. The most frequent congenital heart defects in the treated cohort were tetralogy of Fallot and its variants, followed by single ventricle heart physiology after bidirectional Glenn shunt and/or Fontan-Kreutzer procedures. Right ventricular systolic and pulmonary artery pressure decreased significantly after the intervention (from 68.35 mmHg to 45.8 mmHg and from 47.4 mm Hg to 32 mm Hg, respectively) (p < 0.0001). The initial minimum diameter of the treated pulmonary artery branch increased significantly after the procedure (from 3.98 mm to 9.82 mm, p < 0.0001). The incidence of complications was 8% (n = 2) and the clinical effectiveness of the procedure was good in 22 patients (88%). Conclusions: Stent implant in pulmonary artery branch stenosis is a safe and feasible though challenging technique, with significant clinical and anatomic improvement. The procedure represents an alternative to surgery and decreases the need for reinterventions in patients with congenital heart defects.
Keywords: arterial stent; adult; angioplasty; arterial stent; arterial switch operation; arterial trunk; artery diameter; article; bare metal stent; Blalock Taussig shunt; child; congenital heart disease; coronary stent; coronary stenting; Fallot tetralogy; female; follow up; Fontan procedure; Glenn shunt; human; hypoplastic left heart syndrome; infant; lung artery banding; lung artery pressure; lung perfusion; male; medical device complication; multicenter study; Noonan syndrome; nuclear magnetic resonance imaging; percutaneous transluminal angioplasty; peripheral artery stent; pulmonary artery; pulmonary valve stenosis; self expanding nitinol stent; Williams Beuren syndrome; Advanta V12; CP; Express; Liberte; NuMed; Palmaz Genesis; Sentinol

Maternal use of oral contraceptives and risk of birth defects in Denmark: Prospective, nationwide cohort study - Charlton, B.M.; Mølgaard-Nielsen, D.; Svanström, H.; Wohlfahrt, J.; Pasternak, B.; Melbye, M. (BMJ (Online), 2016)
Study question Is oral contraceptive use around the time of pregnancy onset associated with an increased risk of major birth defects? Methods In a prospective observational cohort study, data on oral contraceptive use and major birth defects were collected among 880 694 live births from Danish registries between 1997 and 2011. We conservatively assumed that oral contraceptive exposure lasted up to the most recently filled prescription. The main outcome measure was the number of major birth defects throughout one year follow-up (defined according to the European Surveillance of Congenital Anomalies classification). Logistic regression estimated prevalence odds ratios of any major birth defect as well as categories of birth defect subgroups. Study answer and limitations Prevalence of major birth defects (per 1000 births) was consistent across each oral contraceptive exposure group (25.1, never users; 25.0, use >3 months before pregnancy onset (reference group); 24.9, use 0-3 months before pregnancy onset (that is, recent use); 24.8, use after pregnancy onset). No increase in prevalence of major birth defects was seen with oral contraceptive exposure among women with recent use before pregnancy (prevalence odds ratio 0.98 (95% confidence interval 0.93 to 1.03)) or use after pregnancy onset (0.95 (0.84 to 1.08)), compared with the reference group. There was also no increase in prevalence of any birth defect subgroup (for example, limb defects). It is unknown whether women took oral contraceptives up to the date of their most recently filled prescription. Also, the rarity of birth defects made disaggregation of the results difficult. Residual confounding was possible, and the analysis lacked information on folate, one of the proposed mechanisms. What this study adds Oral contraceptive exposure just before or during pregnancy does not appear to be associated with an increased risk of major birth defects. Funding, competing interests, data sharing BMC was funded by the Harvard T H Chan School of Public Health's Maternal Health Task Force and Department of Epidemiology Rose Traveling Fellowship; training grant T32HD060454 in reproductive, perinatal, and paediatric epidemiology and award F32HD084000 from the Eunice Kennedy Shriver National Institute of Child Health and Human Development; and grant T32CA09001 from the National Cancer Institute. The authors have no competing interests or additional data to share.
Keywords: oral contraceptive agent; abdominal wall defect; adult; article; cohort analysis; congenital heart malformation; congenital malformation; controlled study; Denmark; digestive system malformation; disease association; ear malformation; eye malformation; face malformation; female; follow up; gastroschisis; genital malformation; human; hypoplastic left heart syndrome; induced abortion; infant; limb malformation; live birth; major clinical study; neck malformation; nervous system malformation; observational study; oral contraceptive use; pregnancy; prescription; prevalence; priority journal; propensity score; prospective study; register; respiratory tract malformation; stillbirth; urinary tract malformation

Effect of Tadalafil on Myocardial and Endothelial Function and Exercise Performance After Modified Fontan Operation - Sabri, M.-R.; Zolfi-Gol, A.; Ahmadi, A.; Haghjooy-Javanmard, S. (Pediatric Cardiology, 2016)
Better postoperative management of patients who have undergone single ventricle (SV) Fontan procedure could potentially reduce long-term complications and improve the quality of life for patients. The present study determined the effect of tadalafil on myocardial and endothelial function and exercise performance after modified Fontan operation. Patients who had undergone SV modified Fontan operation were enrolled in this clinical trial. The demographic characteristics of the patients were recorded. Before administration of tadalafil and after the trial, ventricular function (MPI, EF, FS, E/A, VTI), exercise performance, and endothelial function were evaluated for sonographic and biochemical markers (FMD, IMT, ICAM, VCAM, NO) using echocardiography, exercise testing, vascular ultrasonography, and biochemical measurements, respectively. A single dose of tadalafil of 1 mg/kg was administered daily for 6 weeks, and the functional class of the patients before and after tadalafil was determined. A total of 15 patients completed this clinical trial. Tadalafil was shown to have a significant effect on myocardial function, exercise performance, and improvement in NYHA functional class (p < 0.05) of study population. It had no significant effect on the biochemical variables and endothelial function except for IMT (p > 0.05), which decreased significantly after tadalafil administration (p < 0.05). The findings indicate that tadalafil is a safe, well-tolerated agent for the use after modified Fontan operation to improve myocardial function and exercise performance and possibly reduce long-term morbidity and mortality of patients. More conclusive results could be obtained from further study with a larger sample size and long-term follow-up.
Keywords: biochemical marker; intercellular adhesion molecule; lymphocyte antigen; nitric oxide; tadalafil; unclassified drug; vascular cell adhesion molecule; adolescent; arterial wall thickness; article; blood vessel parameters; cell function; clinical article; demography; endothelial function; exercise; female; flow mediated dilatation; follow up; Fontan procedure; heart function; heart ventricle function; human; male; modified fontan operation; morbidity; mortality; New York Heart Association class; single drug dose

Effect of Sildenafil on Pressure–Volume Loop Measures of Ventricular Function in Fontan Patients - Butts, R.J.; Chowdhury, S.M.; Baker, G.H.; Bandisode, V.; Savage, A.J.; Atz, A.M. (Pediatric Cardiology, 2016)
Sildenafil has been reported to improve exercise capacity in Fontan patients, but the physiologic mechanisms behind these findings are not completely understood. The objective of this study was to study the acute effect of sildenafil on pressure–volume loop (PVL) measures of ventricular function in Fontan patients. Patients after Fontan operation who were presenting for a clinically indicated catheterization were enrolled. Patients were randomized in a double-blinded fashion to receive placebo (n = 9) or sildenafil (n = 10) 30–90 min prior to catheterization. PVLs were recorded using microconductance catheters at baseline and after infusion of dobutamine (10 mcg/kg/min). The primary outcome was change in ventriculoarterial (VA) coupling. For the entire cohort, VA coupling trended toward improvement with dobutamine (1.4 ± 0.4 to 1.8 ± 0.9, p = 0.07). End-systolic elastance showed improvement (2.6 ± 0.9 to 3.8 ± 1.4 mmHg m2/ml, p < 0.01) with dobutamine infusion. The cohorts had similar VA coupling at baseline (p = 0.32), but the sildenafil cohort trended toward having less of an improvement in VA coupling with dobutamine stress (p = 0.06). There were no differences between PVL measures of systolic or diastolic function between treatment groups, both at baseline and after dobutamine infusion. Patients with Fontan circulation had improved contractility and trended toward improvement in VA coupling with dobutamine stress. Acute sildenafil administration was not associated with improved PVL measurements of ventricular function in this population. These results suggest that clinical improvements seen with administration of sildenafil in Fontan patients are not associated with an acute improvement in ventricular function. Clinical Trial Registration: www.clinicaltrials.gov; Clinicaltrials.gov Identifier: NCT01815502.
Keywords: NCT01815502; dobutamine; placebo; sildenafil; article; catheter; catheterization; child; clinical article; controlled study; double blind procedure; Fontan procedure; heart muscle contractility; heart ventricle function; human; measurement; outcome assessment; pressure volume curve; pressure volume loop; randomized controlled trial

A Pilot Study of Antithrombin Replacement Prior to Cardiopulmonary Bypass in Neonates - Niebler, R.A.; Woods, K.J.; Murkowski, K.; Ghanayem, N.S.; Hoffman, G.; Mitchell, M.E.; Punzalan, R.C.; Scott, J.P.; Simpson, P.; Tweddell, J.S. (Artificial Organs, 2016)
Neonates have low levels of antithrombin. Inadequate anticoagulation during cardiopulmonary bypass (CPB) due to low antithrombin activity may result in a poor preservation of the coagulation system during bypass. We hypothesize that antithrombin replacement to neonates prior to CPB will preserve the hemostatic system and result in less postoperative bleeding. A randomized, double-blinded, placebo-controlled pilot study of antithrombin replacement to neonates prior to CPB was conducted. Preoperative antithrombin levels determined the dose of recombinant antithrombin or placebo to be given. Antithrombin levels were measured following the dosing of the antithrombin/placebo, after initiation of bypass, near the completion of bypass, and upon intensive care unit admission. Eight subjects were enrolled. No subject had safety concerns. Mediastinal exploration occurred in two antithrombin subjects and one placebo subject. Antithrombin activity levels were significantly higher in the treated group following drug administration; levels continued to be higher than preoperatively but not different from the placebo group at all other time points. Total heparin administration was less in the antithrombin group; measurements of blood loss were similar in both groups. A single dose of recombinant antithrombin did not maintain 100% activity levels throughout the entire operation. Although no safety concerns were identified in this pilot study, a larger trial is necessary to determine clinical efficacy.
Keywords: NCT01158729; antithrombin; heparin; placebo; recombinant antithrombin; recombinant protein; unclassified drug; aorta anomaly; aortic arch interruption; arterial switch operation; article; blood clotting; bypass surgery; cardiopulmonary bypass; clinical article; clinical effectiveness; controlled study; disease control; double blind procedure; drug efficacy; feasibility study; great vessels transposition; human; hypoplastic left heart syndrome; intensive care; newborn; pilot study; postoperative hemorrhage; priority journal; randomized controlled trial; risk reduction

Half a century's experience with the superior cavopulmonary (classic glenn) shunt - Zahr, R.A.; Kirshbom, P.M.; Kopf, G.S.; Sainathan, S.; Steele, M.M.; Elder, R.W.; Karimi, M. (Annals of Thoracic Surgery, 2016)
Background Five decades after its introduction, the Glenn shunt remains an integral step for patients undergoing single-ventricle palliation. We performed a longitudinal follow-up of the original cohort of patients who underwent Glenn shunt. Methods We performed a retrospective study of the original cohort of patients who underwent Glenn shunt at Yale between 1958 and 1988. Electronic medical records and chart review up to current era were used to collect data. Results Ninety-one patients underwent a Glenn shunt at an average age of 6.6 ± 2.5 years, of which 89 were classic Glenn shunts. Median overall survival was 43 years (range, 2 to 56; 95% confidence interval [CI], 39.5 to 46.5) while median survival from the Glenn shunt was 31.4 years (range, 0 to 45; 95% CI, 23.9 to 38.9). Forty-six patients died, 7 in the early postoperative period and 39 late deaths. Twenty-six patients were lost to follow-up. Nineteen patients remain alive with active clinical follow-up, 6 of whom still live with their classic Glenn shunt without conversion to bidirectional Glenn. Twenty-six patients (31%) developed pulmonary arteriovenous fistula with 11 patients (42%) requiring coil embolization. No patient developed thrombosis of the Glenn shunt. There were a total of 28 patients who developed arrhythmias, mostly in the tricuspid atresia group (n = 16), with the majority being atrial tachyarrhythmias (48%). Sixteen patients required permanent pacemaker placement for sinus node dysfunction. Conclusions The Glenn shunt continues to provide excellent staged palliation in single-ventricle patients and a bridge to two-ventricle repair. Arrhythmias and pulmonary arteriovenous fistulas were common among single-ventricle cohort. Quality-of-life evaluation of the surviving patients would be an important outcome measure for future investigation.
Keywords: aortopulmonary shunt; article; artificial heart pacemaker; Blalock Taussig shunt; child; cohort analysis; coil embolization; electronic medical record; follow up; Fontan procedure; Glenn shunt; heart arrhythmia; heart single ventricle; human; long term survival; major clinical study; medical record review; overall survival; palliative therapy; postoperative complication; postoperative period; priority journal; pulmonary arteriovenous fistula; pulmonary valve prosthesis; retrospective study; sinus node disease; survival rate; tachycardia; treatment outcome; tricuspid valve atresia

Selective serotonin reuptake inhibitors and congenital heart anomalies: Comparative cohort studies of women treated before and during pregnancy and their children - Petersen, I.; Evans, S.J.; Gilbert, R.; Marston, L.; Nazareth, I. (Journal of Clinical Psychiatry, 2016)
Background: Large databases and population registers are increasingly used to examine adverse birth outcomes, congenital heart anomalies, in particular, following antidepressant exposures in pregnancy. Yet many studies have failed to account for other characteristics of the women who were prescribed antidepressants. Objective: To examine the characteristics of women who are prescribed selective serotonin reuptake inhibitors (SSRIs) in pregnancy and women who are not, associations between SSRIs prescribed in pregnancy and congenital heart anomalies, and the association between social and lifestyle characteristics of pregnant women and congenital heart anomalies. Method: Using data from The Health Improvement Network primary care database in the United Kingdom between January 1, 1990, and January 31, 2011, we set up a comparative study including 4 cohorts of children of women with and without different antidepressant exposures before and during pregnancy. 5,154 women were receiving SSRIs before pregnancy, 2,776 were receiving SSRIs during pregnancy, 992 were receiving other antidepressants during pregnancy, and 200,213 were receiving no antidepressants before or during pregnancy. Our primary outcome was congenital heart anomalies. Results: Less than 1% of children had a record of congenital heart anomalies within 5 years of birth, and there were no significant differences related to antidepressant exposure in pregnancy (women not prescribed antidepressants versus women prescribed SSRIs in first trimester: odds ratio [OR] = 1.00; 95% CI, 0.65-1.52); however, independent of antidepressant prescribing, diabetes (OR = 2.23; 95% CI, 1.79-2.77), increasing age (OR = 1.01; 95% CI, 1.00-1.02), alcohol problem (OR = 2.58; 95% CI, 1.55-4.29, illicit drug problems (OR = 1.89; 95% CI, 1.09-3.25), and obesity (OR = 1.38; 95% CI, 1.13-1.69) were associated with an increased risk of having a child with congenital heart anomalies. Conclusions: There was no difference in congenital heart anomalies in children born to women with different antidepressant prescribing exposure status. However, we confirmed an increased risk of congenital heart anomalies in children of older women and in children of women with diabetes, a body mass index above 30 kg/m2, and a history of alcohol and illicit drug problems independent of the prescription of antidepressants. Future research in this field must account for these characteristics. On the basis of existing evidence, advising women to stop antidepressant treatment in pregnancy may be counterproductive.
Keywords: amitriptyline; anticonvulsive agent; antidepressant agent; anxiolytic agent; citalopram; clomipramine; dosulepin; escitalopram; fluoxetine; hypnotic agent; illicit drug; lofepramine; neuroleptic agent; paroxetine; psychotropic agent; serotonin uptake inhibitor; sertraline; venlafaxine; adult; aging; alcoholism; aortic arch anomaly; aortic coarctation; aortic stenosis; subvalvular aortic stenosis; aortic valve disease; aortic regurgitation; aortic valve stenosis; article; atrioventricular septal defect; bicuspid aortic valve; body mass; child; cohort analysis; congenital heart malformation; controlled study; cyanotic heart disease; depression; dextrocardia; diabetes mellitus; drug dependence; Ebstein anomaly; Fallot tetralogy; female; first trimester pregnancy; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; human; hypoplastic left heart syndrome; independent variable; lifestyle; major clinical study; male; medical history; medical record; mitral valve regurgitation; obesity; patent foramen ovale; pregnant woman; prenatal drug exposure; prescription; primary medical care; priority journal; pulmonary artery malformation; pulmonary artery stenosis; pulmonary valve atresia; pulmonary valve disease; pulmonary valve stenosis; risk assessment; social aspect; tricuspid valve regurgitation; United Kingdom

Neurocognitive development and behaviour in school-aged children after surgery for univentricular or biventricular congenital heart disease - Sarrechia, I.; Miatton, M.; De Wolf, D.; François, K.; Gewillig, M.; Meyns, B.; Vingerhoets, G. (European Journal of Cardio-thoracic Surgery, 2016)
OBJECTIVES: To assess the long-term neuropsychological and behavioural profile of school-aged children who were treated for univentricular heart (UVH) conditions or biventricular heart defect (BiVH) in infancy in a cross-sectional study design. METHODS: Sixty-three patients, 17 UVH (13 males, 4 females) and 46 BiVH (19 males, 27 females), were assessed at a mean age of 9.1 years (2.2 years) with an intelligence and neuropsychological test battery. Results were compared between subgroups (UVH, BiVH and a healthy control group). Associations between cognitive outcome, medical and socio-demographic factors were explored. Parents completed the Child Behavior Checklist (CBCL). RESULTS: Mean intelligence and neuropsychological scores were found within normal ranges for all diagnostic groups. Significant differences between UVH patients and controls emerged on auditory sustained and alternating attention, fine motor skills, visuospatial information processing, and to a lesser extent, memory performance. Parents of UVH patients reported more externalizing problems and school problems. Patient groups did not differ on neuropsychological outcome measures, nor on behavioural problems as rated by parents. CONCLUSIONS: After Fontan completion, patients at school age display intelligence scores within normal population-based ranges. However, they were found at risk for subtle shortcomings in attention, fine motor skills, visuospatial information processing and externalizing behaviour problems. Considerations pertaining to neurobehavioural outcome in school-aged children are discussed.
Keywords: article; artificial ventilation; brain development; child; child behavior; Child Behavior Checklist; cognition; congenital heart disease; controlled study; cross-sectional study; extracorporeal circulation; female; heart single ventricle; hospitalization; human; information processing; major clinical study; male; memory; motor performance; neuropsychological test; performance; priority journal; school child; special education

Successful bronchoscopy in a pregnant patient with plastic bronchitis - Patil, M.H.; Siddiqi, A.; Jeffrey Mador, M. (Respiratory Medicine Case Reports, 2016)
Plastic bronchitis is a rare disorder, characterized by formation of thick fibrinous bronchial casts which can obstruct the airway and present as a life threatening emergency (1). It is more common in the pediatric population after corrective or palliative surgery for congenital heart disease like fontan procedure but has rarely been reported in adults as well (1). Pregnancy is a relative contraindication for bronchoscopy. Bronchoscopy in the pregnant patient poses significant risks as manipulation of the airway can lead to impaired oxygenation and ventilation. In addition, the drugs used during this procedure to provide sedation can have a direct impact on the developing fetus (2). In spite of these risks bronchoscopy should not be withheld in an emergent situation as it can be a lifesaving measure. We report a case of successful bronchoscopy using Propofol as the sedating agent in a pregnant female with plastic bronchitis who presented with respiratory distress.
Keywords: propofol; adult; article; bronchitis; bronchoscopy; case report; coughing; dyspnea; female; human; hypoxia; medical history; plastic bronchitis; pregnant woman; priority journal; respiratory distress; risk benefit analysis; young adult

Spectrum of heart diseases in children: An echocardiographic study of 1,666 subjects in a pediatric hospital, Yaounde, Cameroon - Chelo, D.; Nguefack, F.; Menanga, A.P.; Um, S.N.; Gody, J.C.; Tatah, S.A.; Ndombo, P.O.K. (Cardiovascular Diagnosis and Therapy, 2016)
Background: Children's health programs in Sub-Saharan Africa have always been oriented primarily to infectious diseases and malnutrition. We are witnessing in the early 21st century an epidemiological transition marked by the decline of old diseases and the identification of new diseases including heart disease. Therefore, it is necessary to describe the spectrum of these diseases in order to better prepare health workers to these new challenges. Methods: We conducted a cross-sectional study focused on heart disease diagnosed by echocardiography in children seen from January 2006 to December 2014 in a pediatric hospital of Yaounde. We collected sociodemographic data and the types of heart disease from registers, patients files as well as the electronic database of echocardiographic records. Results: A total of 2,235 patients underwent echocardiographic examination during the study period including 1,666 subjects with heart disease. Congenital cardiopathies were found in 1,230 (73.8%) patients and acquired abnormalities in 429 (25.8%). Seven children (0.4%) had a combination of both types. Congenital heart defects (CHD) were dominated by ventricular septal defect (VSD). Acquired heart disease was mostly rheumatic valvulopathies. Dyspnea on exertion was the most frequent presenting complaint (87.6%). Discovery of a heart murmur was the principal clinical finding on physical examination (81.4%). The median age was 9 months for congenital heart disease and 132 months for acquired heart disease. Conclusions: As infectious diseases recede and the diagnostic facilities are improving, pediatric heart diseases occupy a more important position in the spectrum of pediatric diseases in our context. However, the ability to evoke the diagnosis remains unsatisfactory by the majority of health personnel and therefore needs to be improved. Apart from congenital heart diseases, the impact of acquired heart diseases, rheumatic valvulopathy being the highest ranking, is remarkable in pediatrics. Awareness of health personnel for better management of child tonsillitis is more than ever a necessity. This preventive attitude of rheumatic heart disease is the main attitude available in our disadvantaged economic environment.
Keywords: acquired heart disease; adolescent; article; awareness; Cameroon; child; childhood disease; clinical feature; congenital heart disease; controlled study; cross-sectional study; dyspnea; echocardiography; endocardial cushion defect; Fallot tetralogy; female; great vessels transposition; heart atrium septum defect; heart disease; heart murmur; heart muscle fibrosis; heart ventricle septum defect; human; infant; lung vein drainage anomaly; major clinical study; male; mitral valve regurgitation; mixed cardiomyopathy; patent ductus arteriosus; patient attitude; physical examination; pulmonary valve stenosis; rheumatic heart disease; tricuspid valve atresia; valvular heart disease

Digoxin use is associated with reduced interstage mortality in patients with no history of arrhythmia after stage i palliation for single ventricle heart disease - Brown, D.W.; Mangeot, C.; Anderson, J.B.; Peterson, L.E.; King, E.C.; Lihn, S.L.; Neish, S.R.; Fleishman, C.; Phelps, C.; Hanke, S.; Beekman, R.H.; Lannon, C.M. (Journal of the American Heart Association, 2016)
Background-Interstage mortality (IM) remains significant after stage 1 palliation (S1P) for single-ventricle heart disease (SVD), with many deaths sudden and unexpected. We sought to determine whether digoxin use post-S1P is associated with reduced IM, utilizing the multicenter database of the National Pediatric Cardiology Quality Improvement Collaborative (NPCQIC). Methods and Results-From June 2008 to July 2013, 816 infants discharged after S1P from 50 surgical sites completed the interstage to stage II palliation, transplant, or IM. Arrhythmia during S1P hospitalization or discharge on antiarrhythmic medications were exclusions (n=270); 2 patients were lost to follow-up. Two analyses were performed: (1) propensity-score adjusted logistic regression with IM as outcome and (2) retrospective cohort analysis for patients discharged on digoxin versus not, matched for surgical site and other established IM risk factors. Of 544 study patients, 119 (21.9%) were discharged on digoxin. Logistic regression analysis with propensity score, site-size group, and digoxin use as predictor variables showed an increased risk of IM in those not discharged on digoxin (odds ratio, 8.6; lower confidence limit, 1.9; upper confidence limit, 38.3; P<0.01). The retrospective cohort analysis for 60 patients on digoxin (matched for site of care, type of S1P, post-S1P ECMO use, genetic syndrome, discharge feeding route, ventricular function, tricuspid regurgitation, and aortic arch gradient) showed 0% IM in the digoxin at discharge group and an estimated IM difference between the 2 groups of 9% (P=0.04). Conclusions-Among SVD infants in the NPCQIC database discharged post-S1P with no history of arrhythmia, use of digoxin at discharge was associated with reduced IM.
Keywords: digoxin; aortic arch; article; cardiovascular mortality; cohort analysis; drug use; extracorporeal oxygenation; female; genetic disorder; heart arrhythmia; heart disease; heart ventricle function; hospital discharge; human; infant; major clinical study; male; palliative therapy; priority journal; retrospective study; risk reduction; single ventricle heart disease; survival rate; tricuspid valve regurgitation

Important knowledge for parents of children with heart disease: parent, nurse, and physician views - Daily, J.; FitzGerald, M.; Downing, K.; King, E.; del Rey, J.G.; Ittenbach, R.; Marino, B. (Cardiology in the young, 2016)
OBJECTIVES: Parental understanding of their children's heart disease is inadequate, which may contribute to poor health outcomes. The purpose of this study was to determine what parental knowledge is important in the care of children with heart disease from the perspective of parents, nurses, and physicians. METHODS: Focus groups were formed with parents of children with single ventricle congenital heart disease (CHD), biventricular CHD, and heart transplantation, and with nurses and physicians who provide care for these children. A nominal group technique was used to identify and prioritise important parental knowledge items and themes. The voting data for each theme were reported by participant type--parent, nurse, and physician--and patient diagnosis--single ventricle CHD, biventricular CHD, and heart transplantation. RESULTS: The following three themes were identified as important by all groups: recognition of and response to clinical deterioration, medications, and prognosis and plan. Additional themes that were unique to specific groups included the following: medical team members and interactions (parents), tests and labs (parents), neurodevelopmental outcomes and interventions (physicians), lifelong disease requiring lifelong follow-up (physicians and nurses), and diagnosis, physiology, and interventions (single ventricle and biventricular CHD). CONCLUSIONS: Parents, nurses, and physicians have both common and unique views regarding what parents should know to effectively care for their children with single ventricle CHD, biventricular CHD, or heart transplantation. Specific targeted parental education that incorporates these findings should be provided to each group. Further development of questionnaires regarding parental knowledge with appropriate content validity is warranted.
Keywords: adolescent; adult; attitude to health; child; congenital heart malformation; female; health personnel attitude; human; infant; male; nurse; parent; physician; preschool child; questionnaire

Quality of Life of Children with Congenital Heart Diseases: A Multicenter Controlled Cross-Sectional Study - Amedro, P.; Dorka, R.; Moniotte, S.; Guillaumont, S.; Fraisse, A.; Kreitmann, B.; Borm, B.; Bertet, H.; Barrea, C.; Ovaert, C.; Sluysmans, T.; De La Villeon, G.; et al. (Pediatric Cardiology, 2015)
To assess the health-related quality of life (QoL) in children with congenital heart diseases (CHD) with a validated questionnaire in comparison with control children. We prospectively recruited 282 children with CHD aged from 8 to 18 years in two tertiary care centers (France and Belgium) and 180 same-age controls in randomly selected French schools. Children’s QoL was self-reported with the KIDSCREEN-52 questionnaire and reported by parents with the KIDSCREEN-27. QoL scores of each dimension were compared between CHD and controls and between the classes of disease severity. Both centers were comparable for most demographic and clinical data. Age- and gender-adjusted self-reported QoL scores were lower in CHD children than in controls for physical well-being (mean ± SEM 45.97 ± 0.57 vs 50.16 ± 0.71, p < 0.0001), financial resources (45.72 ± 0.70 vs 48.85 ± 0.87, p = 0.01), peers/social support (48.01 ± 0.72 vs 51.02 ± 0.88, p = 0.01), and autonomy in the multivariate analysis (47.63 ± 0.69 vs 49.28 ± 0.85, p = 0.04). Parents-reported scores were lower in CHD children for physical (p < 0.0001), psychological well-being (p = 0.04), peers/social support (p < 0.0001), and school environment (p < 0.0001) dimensions. Similarly, the disease severity had an impact on physical well-being (p < 0.001), financial resources (p = 0.05), and peers/social support (p = 0.01) for self-reported dimensions, and on physical well-being (p < 0.001), psychological well-being (p < 0.01), peers/social support (p < 0.001), and school environment (p < 0.001) for parents-reported dimensions. However, in multivariate analysis on self-reported QoL, disease severity was significantly associated with the self-perception dimension only. Self-reported QoL of CHD children was similar to that of same-age healthy children in seven of 10 dimensions, but parents-reported QoL was impaired in four of five dimensions.
Keywords: NCT01202916); anticoagulant agent; beta adrenergic receptor blocking agent; calcium channel blocking agent; dipeptidyl carboxypeptidase inhibitor; diuretic agent; adolescent; adult; article; artificial heart pacemaker; assessment of humans; Belgium; catecholaminergic polymorphic ventricular tachycardia; child; clinical assessment; congenital heart disease; congestive cardiomyopathy; controlled study; coronary artery anomaly; cross-sectional study; demography; disease severity; female; financial management; France; heart single ventricle; heart surgery; heart ventricle septum defect; human; hypertrophic cardiomyopathy; implantable cardioverter defibrillator; KIDSCREEN 27; KIDSCREEN 52; long QT syndrome; major clinical study; male; multicenter study; multivariate analysis; parent; patient autonomy; prospective study; psychological well-being; quality of life; school; scoring system; self report; social support

Obstructive jaundice secondary to Morgagni hernia in an infant with Fontan circulation - Halaweish, I.; Ralls, M.; Siddiqui, S.; Dickinson, C.; Jarboe, M.D. (Pediatric Surgery International, 2015)
The vast majority of congenital diaphragmatic cases present with severe respiratory distress in the immediate neonatal period. Obstructive jaundice secondary to CDH is a rare presenting symptom, previously unreported with Morgagni type hernias which comprise 2 % of all CDHs. Although the safety of minimally invasive repair for CDH has been shown previously, there has been little data on its safety for patients with complex congenital cardiac disease. In this case report, we present an 18-month old infant with Fontan circulation presenting with jaundice secondary to Morgagni hernia who ultimately underwent laparoscopic repair. A brief discussion of the safety of laparoscopic surgery in patients post-Fontan is included.
Keywords: article; case report; child; cholestasis; common bile duct disease; congenital diaphragm hernia; diaphragm hernia; follow up; Fontan procedure; gallbladder disease; heart output; heart surgery; hepatomegaly; human; hyperbilirubinemia; laparoscopic surgery; magnetic resonance cholangiopancreatography; obstructive jaundice; preschool child; priority journal; respiratory distress; safety; vomiting

Berlin heart ventricular assist device as a long-term bridge to transplantation in a Fontan patient with failing single ventricle - Halaweish, I.; Ohye, R.G.; Si, M.S. (Pediatric Transplantation, 2015)
The use of VADs as a BTT in children with heart failure has increased due to enhanced device design and reliability, leading to improved survival, functional capacity, and quality of life. However, the use of VADs in patients with Fontan physiology as a BTT is rare with few case reports. Here, we describe a case of implantation of the Berlin VAD as a BTT for 179 days, one of the longest reported periods of mechanical support, in a child with failing single ventricle.
Keywords: acetylsalicylic acid; bortezomib; dipyridamole; dopamine; immunoglobulin; milrinone; rituximab; warfarin; adolescent; anticoagulant therapy; aortic surgery; artery catheterization; artery reconstruction; article; blood transfusion; case report; congestive heart failure; coughing; desensitization; diuresis; dyspnea; echocardiography; extracorporeal oxygenation; Fontan procedure; heart muscle biopsy; heart right ventricle failure; heart right ventricle function; heart transplantation; hospital discharge; hospitalization; human; hypoplastic left heart syndrome; immunotherapy; international normalized ratio; kidney function; liver function; male; postoperative hemorrhage; postoperative period; pulmonary artery; treatment indication; treatment outcome; ventricular assist device; EXCOR VAD

Neuropsychological status and structural brain imaging in adolescents with single ventricle who underwent the fontan procedure - Bellinger, D.C.; Watson, C.G.; Rivkin, M.J.; Robertson, R.L.; Roberts, A.E.; Stopp, C.; Dunbar-Masterson, C.; Bernson, D.; DeMaso, D.R.; Wypij, D.; Newburger, J.W. (Journal of the American Heart Association, 2015)
Background-Few studies have described the neuropsychological outcomes and frequency of structural brain or genetic abnormalities in adolescents with single ventricle who underwent the Fontan procedure. Methods and Results-In a cross-sectional, single-center study, we enrolled 156 subjects with single ventricle, mean age 14.5±2.9 years, who had undergone the Fontan procedure. Scores in the entire cohort on a standard battery of neuropsychological tests were compared with those of normative populations or to those of a group of 111 locally recruited healthy adolescents. They also underwent brain magnetic resonance imaging and were evaluated by a clinical geneticist. Genetic abnormalities were definite in 16 subjects (10%) and possible in 49 subjects (31%). Mean Full-Scale IQ was 91.6±16.8, mean Reading Composite score was 91.9±17.2, and mean Mathematics Composite score was 92.0±22.9, each significantly lower than the population means of 100±15. Mean scores on other neuropsychological tests were similarly lower than population norms. In multivariable models, risk factors for worse neuropsychological outcomes were longer total support and circulatory arrest duration at first operation, presence of a genetic abnormality, more operations and operative complications, more catheterization complications, and seizure history. The frequency of any abnormality on magnetic resonance imaging was 11 times higher among Fontan adolescents than referents (66% versus 6%); 19 (13%) patients had evidence of a stroke, previously undiagnosed in 7 patients (40%). Conclusions-The neuropsychological deficits and high frequencies of structural brain abnormalities in adolescents who underwent the Fontan procedure highlight the need for research on interventions to improve the long-term outcomes in this highrisk group.
Keywords: academic achievement; adolescent; age distribution; article; attention; cerebrovascular accident; cohort analysis; controlled study; cross-sectional study; executive function; family history; female; Fontan procedure; genetic disorder; heart arrest; heart single ventricle; human; intelligence quotient; major clinical study; male; Mathematics Composite score; memory test; morbidity; neuroimaging; neuropsychological test; nuclear magnetic resonance imaging; operation duration; population research; postoperative complication; priority journal; Reading Composite score; scoring system; seizure; social cognition

Neuropsychological performance of school-aged children after staged surgical palliation of hypoplastic left heart syndrome - Bergemann, A.; Hansen, J.H.; Rotermann, I.; Voges, I.; Scheewe, J.; Otto-morris, C.; Geiger, F.; Kramer, H.-H. (European Journal of Cardio-thoracic Surgery, 2015)
OBJECTIVES: Despite advances in perioperative management during surgical treatment of hypoplastic left heart syndrome (HLHS), patients are still at risk for adverse neurodevelopmental sequelae including cognitive dysfunction. This study aimed to assess a neuropsychological profile of HLHS patients at school age who underwent the Norwood operation between 1996 and 2003 with deep hypothermic circulatory arrest (DHCA) or antegrade selective cerebral perfusion (ASCP), respectively. METHODS: Forty HLHS patients (DHCA: n = 11 and ASCP: n = 29) were compared with healthy controls (DHCA controls: n = 10 and ASCP controls: n = 24), recruited according to age, sex and socioeconomic status. Neuropsychological assessment included non-verbal intelligence (IQ norms) and raw score measures of visual and verbal short- and long-term memory as well as executive functions, processing speed and concentration. Neuropsychological data were correlated with bypass and circulatory arrest times. RESULTS: Compared with control subjects, both patient groups had average non-verbal intelligence scores [DHCA: 102 (72-112) and ASCP: 92 (70-127)], but showed reduced long-term memory capacities and decreased executive performance as well as reduced processing speed. DHCA patients, furthermore, had a reduced visual attention span, and ASCP patients scored less on the verbal learning task than controls. The duration of DHCA and cardiopulmonary bypass (CPB) was associated with visual executive functions and short-term memory. In the DHCA group, the duration of DHCA was correlated with the time to complete the Trail Making Test A measuring visual executive functions (Spearman rank correlation, rS = 0.867, P = 0.018). In patients provided with ASCP, the cumulated CPB duration was negatively correlated with the score of the block span test measuring visual short memory (rS = -0.476, P = 0.020) as well as with the copy score of the Rey Figure assessing visual executive functions (rS = -0.399, P = 0.032). CONCLUSIONS: School-age children with HLHS who underwent the Norwood procedure either with DHCA or ASCP show cognitive impairments compared with healthy controls. Our data indicate deficits in specific cognitive domains such as memory, executive functions and processing speed rather than basic intellectual dysfunction.
Keywords: article; bleeding; brain hemorrhage; brain perfusion; cardiopulmonary bypass; child; cognitive defect; controlled study; deep hypothermic circulatory arrest; executive function; female; focal epilepsy; Fontan procedure; forward heart failure; heart arrhythmia; heart tamponade; human; hypoplastic left heart syndrome; intelligence quotient; long term memory; male; mental health; multiple organ failure; necrotizing enterocolitis; Norwood procedure; palliative therapy; peroperative complication; priority journal; psychologic test; resuscitation; school child; seizure; sepsis; short term memory; shunt occlusion; thrombosis

Direct physician reporting is associated with reductions in radiation exposure in pediatric cardiac catheterizations - Nicholson, G.T.; Gao, K.; In Kim, S.; Kim, D.W.; Vincent, R.N.; Balfour, V.; Petit, C.J. (Catheterization and Cardiovascular Interventions, 2015)
Objective The objective is to quantify radiation dose in children undergoing cardiac catheterization and determine the impact of increased reporting transparency on total radiation exposure. Background: Cardiac catheterization (cath) can result in significant radiation exposure in children. There has been growing interest in quantifying and reducing radiation exposure in pediatric cath procedures. Our center underwent a slight change in practice recently that resulted in direct physician reporting of radiation dose following every case. Methods We reviewed cath procedures across three different eras in four cath categories: post-heart transplant annual cath, unilateral pulmonary artery (PA) stent placement, pre-Fontan cath, and pre-Glenn cath. The eras were defined as: Era 1, 1/2009 - 1/2011; Era 2, 1/2011 - 9/2013; and Era 3, 9/2013 - 5/2014. In Era 3, the physician performing the cath was responsible for reporting the radiation data. Results Across the three eras, there were significant decreases in cumulative air KERMA (mGy) among all four cath categories. From Era 2 to Era 3, the greatest decreases in radiation were noted, particularly in dose area product (cGy·cm2) in the transplant annual evaluation and pre-Glenn cases. In Era 1, 2 cases (1.2%) had a frame rate reduction, while in Era 2, 22 cases (12.0%), and in Era 3, 83 cases (21.6%) had frame rate changes (P < 0.01). Conclusions Increased physician awareness of radiation exposure is associated with a significant reduction in radiation dose across a variety of cath procedures. This is seen not only by the overall reduction in radiation across case types, but also as the frame rate was more frequently changed during individual cases, indicating an important change in physician behavior and practice.
Keywords: angioplasty; article; child; child care; child health; cohort analysis; Fontan procedure; Glenn shunt; heart catheterization; heart transplantation; human; major clinical study; medical practice; physician attitude; protocol compliance; radiation dose; radiation dose reduction; radiation exposure; radiation hazard; retrospective study; risk reduction; voluntary reporting

Transcoronary infusion of cardiac progenitor cells in hypoplastic left heart syndrome: Three-year follow-up of the Transcoronary Infusion of Cardiac Progenitor Cells in Patients with Single-Ventricle Physiology (TICAP) trial - Tarui, S.; Ishigami, S.; Ousaka, D.; Kasahara, S.; Ohtsuki, S.; Sano, S.; Oh, H. (Journal of Thoracic and Cardiovascular Surgery, 2015)
Objectives Our aim was to assess midterm safety and clinical outcomes of intracoronary infusion of cardiosphere-derived cells (CDCs) after staged palliation in patients with hypoplastic left heart syndrome (HLHS). Methods In this prospective, controlled study, 14 consecutive patients with HLHS who were undergoing 2- or 3-stage surgical palliations were assigned to receive intracoronary CDC infusion 1 month after cardiac surgery (n = 7), followed by 7 patients allocated to a control group with standard care alone. The primary end point was to assess procedural feasibility and safety; the secondary end point was to evaluate cardiac function and heart failure status through 36-month follow-up. Results No complications, including tumor formation, were reported within 36 months after CDC infusion. Echocardiography showed significantly greater improvement in right ventricular ejection fraction (RVEF) in infants receiving CDCs than in controls at 36 months (+8.0% ± 4.7% vs +2.2% ± 4.3%; P =.03). These cardiac function improvements resulted in reduced brain natriuretic peptide levels (P =.04), lower incidence of unplanned catheter interventions (P =.04), and higher weight-for-age z score (P =.02) at 36 months relative to controls. As independent predictors of treatment responsiveness, absolute changes in RVEF at 36 months were negatively correlated with age, weight-for-age z score, and RVEF at CDC infusion. Conclusions Intracoronary CDC infusion after staged procedure in patients with HLHS is safe and improves RVEF, which persists during 36-month follow-up. This therapeutic strategy may enhance somatic growth and reduce incidence of heart failure.
Keywords: brain natriuretic peptide; aorta; article; body growth; carcinogenesis; cardiac stem cell; child; clinical article; controlled study; echocardiography; event free survival; extracorporeal oxygenation; female; Fontan procedure; functional status; heart ejection fraction; heart function; heart right ventricle enddiastolic volume; heart right ventricle endsystolic volume; heart single ventricle; heart ventricle function; human; hypoplastic left heart syndrome; lung vascular resistance; male; mean arterial pressure; preschool child; priority journal; quality of life; stem cell transplantation

Transparency in a Pediatric Quality Improvement Collaborative: A Passionate Journey by NPC-QIC Clinicians and Parents - Lihn, S.L.; Kugler, J.D.; Peterson, L.E.; Lannon, C.M.; Pickles, D.; Beekman, R.H. (Congenital Heart Disease, 2015)
Transparency-sharing data or information about outcomes, processes, protocols, and practices-may be the most powerful driver of health care improvement. In this special article, the development and growth of transparency within the National Pediatric Cardiology Quality Improvement Collaborative is described. The National Pediatric Cardiology Quality Improvement Collaborative transparency journey is guided by equal numbers of clinicians and parents of children with congenital heart disease working together in a Transparency Work Group. Activities are organized around four interrelated levels of transparency (individual, organizational, collaborative, and system), each with a specified purpose and aim. A number of Transparency Work Group recommendations have been operationalized. Aggregate collaborative performance is now reported on the public-facing web site. Specific information that the Transparency Work Group recommends centers provide to parents has been developed and published. Almost half of National Pediatric Cardiology Quality Improvement Collaborative centers participated in a pilot of transparently sharing their outcomes achieved with one another. Individual centers have also begun successfully implementing recommended transparency activities. Despite progress, barriers to full transparency persist, including health care organization concerns about potential negative effects of disclosure on reputation and finances, and lack of reliable definitions, data, and reporting standards for fair comparisons of centers. The National Pediatric Cardiology Quality Improvement Collaborative's transparency efforts have been a journey that continues, not a single goal or destination. Balanced participation of clinicians and parents has been a critical element of the collaborative's success on this issue. Plans are in place to guide implementation of additional transparency recommendations across all four levels, including extension of the activities beyond the collaborative to support transparency efforts in national cardiology and cardiac surgery societies.
Keywords: article; cardiologist; congenital heart disease; doctor patient relationship; health care organization; health care quality; heart single ventricle; human; hypoplastic left heart syndrome; information processing; Internet; parent; physician; priority journal; total quality management

Health-Related Quality of Life in Adult Survivors After the Fontan Operation - Kukreja, M.; Bryant, A.S.; Cleveland, D.C.; Dabal, R.; Hingorani, N.; Kirklin, J.K. (Seminars in Thoracic and Cardiovascular Surgery, 2015)
The primary objective of this study was to ascertain the long-term health-related quality of life (HRQOL) of adult patients who underwent a childhood Fontan operation for palliation of univentricular cardiac anomalies. The secondary objective was to compare the long-term HRQOL of Fontan survivors to that of pediatric heart transplant recipients. This cross-sectional study examined adult survivors (>19 years) who underwent a Fontan operation during childhood (Fontan group) or a pediatric heart transplant (HT group) between 1988 and 2011 (23-year span). HRQOL was assessed using the short form 36 survey. The study group consisted of 49 Fontan group patients and 13 HT group patients who responded to the survey. HRQOL scores of the Fontan group were similar to those of an age-controlled healthy US population in social and mental functioning, energy or vitality, and overall mental component score (P ≥ 0.2). However, Fontan scores in physical functioning, bodily pain, general health, and overall by physical component were significantly lower than those of the age-controlled US population (P < 0.05). No differences were identified between Fontan and HT patients. This favorable life-satisfaction period (average 18 years) should be considered when informing patients and families of expectations with the Fontan pathway vs certain higher-risk procedures.
Keywords: adolescent; adult; article; child; comparative study; controlled study; cross-sectional study; energy; female; Fontan procedure; graft recipient; heart graft; heart single ventricle; human; life satisfaction; major clinical study; male; mental function; pain; palliative therapy; pediatric surgery; physical activity; preschool child; quality of life; school child; Short Form 36; social interaction; survivor; United States

Prenatal Counseling and Care for Single-Ventricle Heart Disease: One Center's Model for Care - Lafranchi, T.; Lincoln, P. (Critical care nurse, 2015)
Advances in prenatal imaging allow early detection of single-ventricle congenital heart disease, which may enhance prenatal care and maximize care options and decision making. Boston Children's Hospital's Advanced Fetal Care Center and fetal cardiology program provide prenatal counseling and care for single-ventricle congenital heart disease. Key points for optimal prenatal counseling and education include explanation of the diagnosis, delivery, the first surgery, cardiac neurodevelopmental issues, feeding and growth issues, quality of life and long-term care, family stressors, and fetal cardiac intervention. Such counseling and education help families make the difficult decisions required in this situation.
Keywords: counseling; female; fetus; heart disease; hospital; human; intensive care unit; obstetric delivery; pregnancy; prenatal care; prenatal diagnosis; procedures; prognosis

Committed to Life: Adolescents' and Young Adults' Experiences of Living with Fontan Circulation - Berghammer, M.C.; Brink, E.; Rydberg, A.M.; Dellborg, M.; Ekman, I. (Congenital Heart Disease, 2015)
Background: Single ventricle defects are among the most complex congenital heart defects and the development of advanced surgical procedures in recent decades has created the first generation of adolescents and young adults living with this condition. Yet little is known about how these individuals experience life and what impact the heart defect has on their life in general. Objective: The aim was to illuminate and gain a deeper understanding of adolescents' and young adults' experiences of living with a surgically palliated univentricular heart. Design: Seven open-ended in-depth interviews were conducted, transcribed, and analyzed according to the henomenological hermeneutical method. All adolescents and young adults operated before 1995 according to the Fontan procedure or the total cavo-pulmonary connection procedure at one pediatric cardiology unit were included in the study. They were 17-32 years of age (median age 22 years). Results: The interpretation of the interview transcripts showed that the participants experienced living with a surgically palliated univentricular heart in terms of feeling exceptional, strong, and healthy. This was supported by two structural analyses, where three themes emerged: happiness over being me, focusing on possibilities, and being committed to life. Conclusion: Living with a Fontan circulation included negative experiences but the analyses clearly demonstrated a feeling of being strong and healthy. An appreciation of having survived and being committed to life was found to be an integral part of the development of the interviewees' existential growth. This probably strengthens them further in their ability to balance expectations and hurdles in life. This study provides valuable insights into the experience of patients after the Fontan procedure and the importance of a positive health care environment throughout their lives.
Keywords: adolescent; adult; ambivalence; article; attitude to life; clinical article; cognition; confusion (uncertainty); controlled study; disease control; fear; female; Fontan procedure; happiness; heart single ventricle; human; male; patient satisfaction; patient worry; personal experience; physical mobility; priority journal; self concept; social acceptance; wisdom; young adult

Periconceptional Folic Acid Supplementation and Infant Risk of Congenital Heart Defects in Norway 1999-2009 - Leirgul, E.; Gildestad, T.; Nilsen, R.M.; Fomina, T.; Brodwall, K.; Greve, G.; Vollset, S.E.; Holmstrøm, H.; Tell, G.S.; Øyen, N. (Paediatric and Perinatal Epidemiology, 2015)
Background The birth prevalence of congenital heart defects (CHDs) has decreased in Canada and Europe. Recommended intake of folic acid in pregnancy is a suggestive risk-reducing factor for CHDs. We investigated the association between periconceptional intake of folic acid supplements and infant risk of CHDs. Methods Information on maternal intake of folic acid supplements before and during pregnancy in the Medical Birth Registry of Norway 1999-2009 was updated with information on CHD diagnoses from national health registers and the Cardiovascular Diseases in Norway Project. The association between folic acid intake and infant risk of CHD was estimated as relative risk (RR) with binomial log linear regression. Results Among 517784 non-chromosomal singleton births, 6200 children were identified with CHD and 1153 with severe CHD. For all births, 18.4% of the mothers initiated folic acid supplements before pregnancy and 31.6% during pregnancy. The adjusted RR for severe CHD was 0.99 [95% confidence interval [CI] 0.86, 1.13] comparing periconceptional intake of folic acid with no intake. Specifically, RR for conotruncal defects was 0.99 [95% CI 0.80, 1.22], atrioventricular septal defects 1.19 [95% CI 0.78, 1.81], left ventricular outflow tract obstructions 1.02 [95% CI 0.78, 1.32], and right ventricular outflow tract obstructions 0.97 [95% CI 0.72, 1.29]. Birth prevalence of septal defects was higher in the group exposed to folic acid supplements with RR 1.19 [95% CI 1.10, 1.30]. Conclusions Periconceptional folic acid supplement use showed no association with severe CHDs in the newborn. An unexpected association with an increased risk of septal defects warrants further investigation.
Keywords: aortic coarctation; aortic valve stenosis; article; atrioventricular septal defect; Canada; cardiovascular disease; cause of death; congenital heart malformation; controlled study; diet supplementation; disease severity; Ebstein anomaly; Europe; Fallot tetralogy; folic acid supplementation; great vessels transposition; heart atrium septum defect; heart left ventricle outflow tract obstruction; heart right ventricle double outlet; heart septum defect; interventricular septum; heart ventricle septum defect; human; hypoplastic left heart syndrome; lung vein drainage anomaly; major clinical study; Norway; patent ductus arteriosus; phenotype; prevalence; protein synthesis; pulmonary valve atresia; pulmonary valve stenosis; risk factor; risk reduction

Does exercise training improve cardiopulmonary fitness and daily physical activity in children and young adults with corrected tetralogy of Fallot or Fontan circulation? A randomized controlled trial - Duppen, N.; Etnel, J.R.; Spaans, L.; Takken, T.; Van Den Berg-Emons, R.J.; Boersma, E.; Schokking, M.; Dulfer, K.; Utens, E.M.; Helbing, W.; Hopman, M.T. (American Heart Journal, 2015)
Background Many patients with congenital heart disease do not meet current public health guidelines to participate in moderate-to-vigorous physical activity for ≥60 minutes per day. They are less fit than their healthy peers. We hypothesized that exercise training would increase cardiopulmonary fitness and daily physical activity in these patients. We therefore assessed effects of an exercise training program on cardiopulmonary fitness and daily physical activity in patients with corrected tetralogy of Fallot (ToF) or Fontan circulation. Methods In a multicenter prospective controlled trial, patients with ToF or Fontan circulation (age 10-25 years) were randomized, 56 patients to the exercise group and 37 to the control group. The exercise group participated in a 12-week standardized aerobic exercise training program. The control group continued lifestyle as usual. Cardiopulmonary exercise testing and activity measurements were performed before and after 12 weeks. Results Peak oxygen uptake increased in the exercise group by 5.0% (1.7 ± 4.2 mL/kg per minute; P =.011) but not in the control group (0.9 ± 5.2 mL/kg per minute; P = not significant). Workload increased significantly in the exercise group compared with the control group (6.9 ± 11.8 vs 0.8 ± 13.9 W; P =.047). Subgroup analysis showed a significant increase in pre-to-post peak oxygen uptake in the exercise group of ToF patients but not in the exercise group of Fontan patients. Percentage of measured time spent in moderate-to-vigorous activity at baseline was 13.6% ± 8.6%, which did not significantly change after training. Conclusions Aerobic exercise training improved cardiopulmonary fitness in patients with ToF but not in patients with Fontan circulation. Exercise training did not change daily physical activity.
Keywords: NTR2731; adolescent; adult; aerobic exercise; article; cardiopulmonary exercise test; cardiorespiratory fitness; cardiovascular magnetic resonance; child; congenital heart disease; controlled study; Fallot tetralogy; female; Fontan circulation; heart rehabilitation; heart stroke volume; heart work; human; lifestyle; lung gas exchange; major clinical study; male; multicenter study; outcome assessment; oxygen consumption; patient compliance; physical activity; physical performance; priority journal; program efficacy; program evaluation; prospective study; randomized controlled trial; school child; single blind procedure; treatment duration; whole body MRI; young adult

Iatrogenic aortopulmonary communications after transcatheter interventions on the right ventricular outflow tract or pulmonary artery: Pathophysiologic, diagnostic, and management considerations - Torres, A.; Sanders, S.P.; Vincent, J.A.; El-Said, H.G.; Leahy, R.A.; Padera, R.F.; McElhinney, D.B. (Catheterization and Cardiovascular Interventions, 2015)
Objectives To investigate the spectrum, etiology, and management of traumatic aortopulmonary (AP) communications after transcatheter interventions on the pulmonary circulation. Background An iatrogenic AP communication is an unusual complication after balloon pulmonary artery (PA) angioplasty or stenting, or transcatheter pulmonary valve replacement (TPVR). However, with the increasing application of transcatheter therapies for postoperative PA stenosis and right ventricular outflow tract (RVOT) dysfunction, including percutaneous pulmonary valve replacement, consideration of the etiology, diagnosis, and management of this problem is important for interventional cardiologists performing such procedures. Methods and Results We present three new cases, as well as gross anatomy and histopathology data, related to AP communications after PA interventions. We also review the literature relevant to this topic. Including these new cases, there have been 18 reported cases of iatrogenic AP communication after transcatheter interventions on the PAs or RVOT, primarily patients with transposition of the great arteries who underwent PA angioplasty after an arterial switch operation, or after TPVR in patients who had undergone a Ross procedure. The likely cause of such defects is PA trauma plus distortion of the neo-aortic anastomosis resulting from angioplasty or stenting of the RVOT or central PAs, with subsequent dissection through the extravascular connective tissue and into the closely adjacent vessel through the devitalized tissue at the anastomosis. Conclusions Cardiologists performing PA or RVOT interventions should be aware of the possibility of a traumatic AP communication and consider this diagnosis when confronted with suggestive signs and symptoms.
Keywords: adult; angioplasty; arterial switch operation; artery catheterization; article; ascending aorta; cardiac conduit; case report; child; stent graft; Doppler echocardiography; echocardiography; Fontan procedure; great vessels transposition; heart left ventricle outflow tract obstruction; heart murmur; heart right ventricle outflow tract; heart surgery; heart valve prosthesis; human; hypotension; iatrogenic aortopulmonary communication; lung artery pressure; lung circulation; lung edema; male; pulmonary angioplasty; pulmonary artery; pulmonary artery stenosis; pulmonary valve replacement; Ross Konno procedure; Ross procedure; transcatheter pulmonary valve replacement; vascular disease; vascular stent; young adult

Fetal Growth and Neurodevelopmental Outcome in Congenital Heart Disease - Williams, I.A.; Fifer, W.P.; Andrews, H. (Pediatric Cardiology, 2015)
We evaluated differences in growth between fetuses with and without congenital heart disease (CHD) and tested associations between growth and early childhood neurodevelopment (ND). In this prospective cohort study, fetuses with hypoplastic left heart syndrome (HLHS), transposition of the great arteries (TGA), and tetralogy of Fallot (TOF) and controls had biparietal diameter (BPD), head (HC) and abdominal circumference (AC), femur length (FL), and estimated fetal weight (EFW) recorded serially during pregnancy at 18–26 weeks GA (F1), at 27–33 weeks GA (F2), and at 34–40 weeks GA (F3). CHD subjects underwent Bayley Scales of Infant Development-III ND testing at 18 months. Differences between CHD fetuses and controls were assessed using t tests and generalized linear modeling. Correlations between biometry and ND informed regression modeling. We enrolled 41 controls and 68 fetuses with CHD (N = 24 HLHS, N = 21 TGA, N = 23 TOF), 46 of whom had ND scores available. At 18–26 weeks, CHD fetuses were smaller than controls in all biometric parameters. Differences in growth rates were observed for HC, BPD, and AC, but not for FL or EFW. Cognitive score correlated with HC/AC at F2 (r = −0.33, P = 0.04) and mean HC/AC across gestation (r = −0.35, P = 0.03). Language correlated with FL/BPD at F2 (r = 0.34, P = 0.04). In stepwise linear regression, mean HC/AC predicted Cognition (B = −102, P = 0.026, R2 = 0.13) and FL/BPD at F2 predicted Language score (B = 127, P = 0.03, R2 = 0.12). Differences in growth between CHD fetuses and controls can be measured early in pregnancy. In CHD fetuses, larger abdominal relative to head circumference is associated with better 18-month neurodevelopment.
Keywords: abdominal circumference; article; Bayley Scales of Infant Development; biparietal distance; cognition assessment; cohort analysis; congenital heart disease; controlled study; disease association; Fallot tetralogy; female; femur; fetus; fetus growth; fetus weight; great vessels transposition; growth rate; head circumference; human; hypoplastic left heart syndrome; language; low birth weight; major clinical study; male; nerve cell differentiation; newborn; pregnancy; prospective study

Hybrid procedure and collaborative approach for hypoplastic left heart syndrome - Kim, S.-H. (General Thoracic and Cardiovascular Surgery, 2015)
Keywords: nitrogen; article; cardiologist; cardiovascular surgery; congenital heart disease; echocardiography; Fontan procedure; interatrial septum; heart catheterization; heart left atrium; human; hybrid; hypoplastic left heart syndrome; intact heart atrium septum; interventional cardiovascular procedure; lung artery banding; newborn; Norwood procedure; pediatric cardiology; procedures; teamwork

Older age at completion of fontan procedure: Is associated with improved percentage of predicted maximum oxygen uptake - Bolin, E.H.; Maskatia, S.A.; Tate, A.L.; Petit, C.J. (Texas Heart Institute Journal, 2015)
We tested the hypothesis that later completion of the Fontan procedure is associated with improved exercise capacity in the current period of staged single-ventricle palliation. We performed a retrospective study, in Fontan patients, of exercise stress test data from April 2003 through March 2011. Patients were included if they had received staged palliations in accordance with current surgical strategy, defined as the performance of a superior cavopulmonary connection at ≤1 year of age, followed in subsequent years by Fontan completion. Patients with a pacemaker or respiratory exchange ratio <1 were excluded. Early and late Fontan groups were created on the basis of whether Fontan completion had been performed at <4 or ≥ 4 years of age. The primary predictor variable was age at Fontan completion, and the primary marker of exercise performance was the percentage of predicted maximum oxygen consumption. During the study period, 55 patients were identified (mean age, 11.7 ± 2.8 yr). Older age at Fontan completion correlated positively with higher percentages of predicted maximum oxygen consumption (R=0.286, P=0.034). Patients in whom Fontan completion was performed at ≥4 years of age had higher percentages of predicted maximum oxygen consumption than did those in whom completion was at <4 years of age (84.4 ± 21.5 vs 72.9 ± 18.1; P=0.041). Later Fontan completion might be associated with improved exercise capacity in patients palliated in accordance with contemporary surgical strategy.
Keywords: age distribution; anaerobic threshold; article; body mass; body surface; cavopulmonary connection; child; clinical feature; computer assisted tomography; echocardiography; exercise; exercise test; female; fenestration; Fontan procedure; heart rate; human; lung gas exchange; lung vascular resistance; major clinical study; male; metabolic parameters; mitral valve regurgitation; nuclear magnetic resonance imaging; oxygen consumption; oxygen saturation; preschool child; retrospective study; systolic dysfunction; treadmill exercise; tricuspid valve regurgitation

Parental mental health moderates the efficacy of exercise training on health-related quality of life in adolescents with congenital heart disease - Dulfer, K.; Duppen, N.; Van Dijk, A.P.J.; Kuipers, I.M.; Van Domburg, R.T.; Verhulst, F.C.; Van der Ende, J.; Helbing, W.A.; Utens, E.M.W.J. (Pediatric Cardiology, 2015)
To evaluate the moderating influence of parental variables on changes in health-related quality of life (HRQoL) in adolescents with Tetralogy of Fallot (ToF) or a Fontan circulation after participation in standardized exercise training. A multicenter randomized controlled trail in which 56 patients, aged 10–15, were randomly allocated (stratified by age, gender, and congenital heart disease) to a 12-week period with either: (a) 3 times per week standardized exercise training or (b) care-as-usual (randomization ratio 2:1). Adolescents and their parents filled in online questionnaires at baseline and at 12-week follow-up. In this randomized controlled trail, primary analyses involved influence of parental mental health and parental social support for exercise on changes in the TNO/AZL Child Quality of Life Questionnaire Child Form at followup. Secondary analyses concerned comparing levels of parental characteristics with normative data. Compared with controls, adolescents in the exercise group reported a decrease in social functioning when their parents had more anxiety/insomnia or severe depression themselves. Adolescents also reported a decrease in social functioning when their parents showed poorer overall mental health themselves. Parents reported comparable or even better mental health compared with normative data. The effect of a standardized exercise program on HRQoL changes in adolescents with ToF or a Fontan circulation is moderated by parental mental health, more specifically by parental anxiety/insomnia and severe depression. The trial registration number of this article is NTR2731 (www.trialregister.nl).
Keywords: NTR2731; adolescent; anxiety; article; child; congenital heart disease; controlled study; depression; disease severity; exercise; Fallot tetralogy; female; human; insomnia; major clinical study; male; mental health; multicenter study; parental mental health; quality of life; questionnaire; randomized controlled trial; social status; social support; TNO/AZL Child Quality of Life Questionnaiore Child Form

Ventricular function and cardiac reserve in contemporary Fontan patients - Bossers, S.S.M.; Kapusta, L.; Kuipers, I.M.; Van Iperen, G.; Moelker, A.; Kroft, L.J.M.; Romeih, S.; De Rijke, Y.; Ten Harkel, A.D.J.; Helbing, W.A. (International Journal of Cardiology, 2015)
Background/objective Total cavopulmonary connection (TCPC) has been the preferred treatment for patients with univentricular hearts. Current TCPC-techniques are the intra-atrial lateral tunnel (ILT) and the extracardiac conduit (ECC). We aimed to determine ventricular function during rest and stress, and to compare results for both techniques and for left (LV) versus right ventricular (RV) dominance. Methods 99 patients, aged 12.5 ± 4.0 years underwent echocardiography and magnetic resonance imaging (MRI), and 69 patients underwent stress MRI. Results Echocardiography showed impaired systolic and diastolic function. MRI parameters were comparable between ILT and ECC at rest. During dobutamine there was a decrease in end-diastolic volume (EDVi) (91 ± 21 vs. 80 ± 20 ml/m2 p < 0.001). Ejection fraction (EF) and cardiac index (CI) during dobutamine were lower for ILT patients (59 ± 11 (ILT) vs. 64 ± 7% (ECC), p = 0.027 and 4.2 ± 1.0 (ILT) vs. 4.9 ± 1.0 L/min/m2 (ECC), p = 0.006), whereas other parameters were comparable. TEI-index was higher in ILT-patients (0.72 ± 0.27 (ILT) vs. 0.56 ± 0.22 (ECC), p = 0.002). Diastolic function was frequently impaired in patients with a dominant RV (67% (RV) vs. 39% (LV), p = 0.011). Patients with dominant LV's had smaller end-systolic volume (ESVi) (40 ± 13 (LV) vs. 47 ± 16 (RV) ml/m2, p = 0.030) and higher EF (55 ± 8 (LV) vs. 49 ± 9 ml/m2 (RV), p = 0.001) and contractility (2.3 ± 0.8 (LV) vs. 1.9 ± 0.7 mm Hg/ml/m2 (RV), p = 0.050) during rest and higher EF during dobutamine (63 ± 8 (LV) vs. 58 ± 10 ml/m2 (RV), p = 0.043). Conclusion Ventricular function is relatively well preserved in modern-day Fontan patients. With dobutamine stress there is a decrease in EDVi. ECC patients have higher CI and EF during stress. Patients with a dominant RV have lower systolic, including impaired contractility, and diastolic function.
Keywords: dobutamine; age distribution; article; child; clinical effectiveness; diastole; drug effect; echocardiography; female; Fontan procedure; cardiac index; heart left ventricle ejection fraction; heart left ventricle enddiastolic volume; heart left ventricle function; heart right ventricle ejection fraction; heart right ventricle enddiastolic volume; heart right ventricle function; heart single ventricle; heart stress; human; major clinical study; male; multicenter study; nuclear magnetic resonance imaging; priority journal; rest; surgical approach; systole

Forty years of quality-of-life research in congenital heart disease: Temporal trends in conceptual and methodological rigor - Bratt, E.-L.; Moons, P. (International Journal of Cardiology, 2015)
Background The first study on quality of life (QoL) in patients with congenital heart disease was published 40 years ago. Since then, the number of QoL articles on these patients has grown exponentially. We conducted a systematic literature review of all empirical studies on QoL in patients with congenital heart disease published since 1974, with the aim of determining the range of conceptual and methodological rigor of studies and identifying temporal trends in these parameters. Methods PubMed, Embase, and Cinahl were searched for empirical studies addressing QoL in children, adolescents, or adults with congenital heart disease, published between January 1, 1974, and December 31, 2014. We applied 10 review criteria that were previously developed by Gill and Feinstein in 1994 and further refined by Moons et al. in 2004. Overall, 234 articles were reviewed. Results We found slight but non-significant temporal improvements in conceptual and methodological rigor and in use of assessment methods. This indicates a trend toward a more professional and exacting approach in QoL assessments. However, the majority of articles still had substantial conceptual and methodological deficits. Furthermore, we observed that citation of the publications of Gill and Feinstein and Moons et al. in published QoL research is associated with higher quality scores, suggesting that these articles have a positive impact on conceptual and methodological caliber. Conclusion Despite 40 years of QoL research in this field, this review shows that major weaknesses in methodological rigor remain highly prevalent, which may make QoL studies inconclusive.
Keywords: aortic coarctation; aortic valve disease; article; atrioventricular septal defect; citation analysis; clinical assessment; concept analysis; congenital heart disease; coronary artery anomaly; differential diagnosis; Ebstein anomaly; Eisenmenger complex; Fallot tetralogy; great vessels transposition; health status; heart right ventricle double outlet; heart ventricle septum defect; human; hypoplastic left heart syndrome; journal impact factor; medical literature; medical research; priority journal; publication; pulmonary hypertension; pulmonary valve atresia; quality of life; systematic review; trend study

Acute ischemic stroke in a child due to basilar artery occlusion treated successfully with a stent retriever - Savastano, L.; Gemmete, J.J.; Pandey, A.S.; Roark, C.; Chaudhary, N. (BMJ Case Reports, 2015)
Ischemic strokes in childhood are rare. Thrombolytic therapy with intravenous (IV) tissue plasminogen activator (tPA) has been the main intervention for the management of pediatric stroke patients, but safety data are lacking and efficacy has been questioned. Recently, successful endovascular treatments for acute ischemic stroke in children have been reported with increasing frequency, suggesting that mechanical thrombectomy can be a safe and effective treatment. We present the case of a 22-month-old child with acute ischemic stroke due to basilar artery occlusion that was successfully treated with a stent retriever.
Keywords: acetylsalicylic acid; biotinidase; nicardipine; warfarin; artery puncture; article; ataxia; basilar artery obstruction; biotinidase deficiency; brain circulus arteriosus; brain infarction; brain ischemia; case report; child; computer assisted tomography; echocardiography; female; follow up; Fontan procedure; gait disorder; guiding catheter; heart atrium septum defect; heart ventricle septum defect; human; intracardiac thrombosis; lung artery banding; magnetic resonance angiography; medical history; mental disease; mesencephalon; microcatheter; muscle tone; nuclear magnetic resonance imaging; physical examination; pons; postoperative period; priority journal; school child; stent retriever; thalamus; tricuspid valve atresia; unsteadiness; vertebral arteriography; Cello; Rebar; Solitaire

Survival and quality of life for children with end-stage heart failure who are not candidates for cardiac transplant - Sabati, A.A.; Szmuszkovicz, J.R.; Herrington, C.; Hermes, M.; Mahmoud, H.A.; Phei Wee, C.; Starnes, V.A.; Menteer, J. (Journal of Heart and Lung Transplantation, 2015)
Background Some pediatric patients referred for heart transplant (HTx) are sub-optimal candidates. Their outcomes without HTx are presumed to be dismal, but have not been well described. Knowledge about their outcomes is critical when weighing the risks between a high-risk transplant and "terminal" palliation. Methods We retrospectively reviewed all HTx referrals from January 2005 to July 2013. We excluded those who were listed for HTx, or who were denied HTx due to being "too well," seeking only those who were in need of but not suitable for HTx. End-points included mortality and length of survival. Results Of 212 referrals, 39 (19%) (age 0 to 19 years, median 3.5 years) were denied HTx for reasons other than being too well. Twenty-eight (72%) had palliated congenital heart disease. Overall mortality during the follow-up period was 38% (n = 15) with a median follow-up time of 195 days (8 to 2,832 days). Ten patients received subsequent cardiac surgery with 1 death (10%) and median follow-up of 2.6 years. Mortality risk was not influenced by age, weight, growth failure, congenital heart disease or single-ventricle physiology. Mechanical ventilation (hazard ratio 6.31, p = 0.001) and inotrope dependence (hazard ratio 4.79, p = 0.006) were associated with the highest risk of mortality. Quality of life was measured with the PedsQL cardiac module and completed by 11 of 16 eligible patients with an overall average score of 70.2 ± 23.9. Conclusions An advanced heart failure program can achieve satisfactory results for pediatric patients who are not suitable candidates for HTx. For some children, high-risk palliative surgery can result in better outcome than high-risk HTx. Mortality was related to the degree of heart failure at presentation rather than underlying heart disease.
Keywords: inotropic agent; adolescent; adult; article; artificial ventilation; body weight; cardiovascular mortality; child; childhood mortality; congenital heart disease; death; end stage heart failure; female; follow up; growth disorder; heart failure; heart single ventricle; heart surgery; heart transplantation; human; infant; inotropism; major clinical study; male; priority journal; quality of life; retrospective study; survival

The prevalence of attention-deficit/hyperactivity disorder following neonatal aortic arch repair - Sistino, J.J.; Atz, A.M.; Simpson, K.N.; Ellis, C.; Ikonomidis, J.S.; Bradley, S.M. (Cardiology in the Young, 2015)
Objective: We sought to determine the prevalence of attention-deficit/hyperactivity disorder in a population of children who underwent neonatal heart surgery involving repair of the aortic arch for Norwood Stage I, interrupted aortic arch, and combined repair of aortic coarctation with ventricular septal defect. Methods: Children between the ages of 5 and 16 were surveyed using the ADHD-IV and the Child Heath Questionnaire-50. Classification as attention-deficit/hyperactivity disorder was defined for this study as either a parent-reported diagnosis of attention-deficit/hyperactivity disorder or ADHD-IV inattention score of ≥93 percentile. Results: Of the 134 surveys, 57 (43%) were returned completed. A total of 25 (44%) children either had a diagnosis of attention-deficit/hyperactivity disorder and/or ADHD-IV inattention score ≥93 percentile. Eleven of the 13 (85%) children with interrupted aortic arch, 3 of the 7 (42.9%) children with combined coarctation/ventricular septal defect repair, and 9 of the 33 (27.3%) children with hypoplastic left-heart syndrome were classified as having attention-deficit/hyperactivity disorder. Only 7 of the 25 (28%) children received medical treatment for this condition. Quality of life indicators in the Child Heath Questionnaire-50 Questionnaire were highly correlated with the ADHD-IV scores. Conclusion: The risks for the development of attention-deficit/hyperactivity disorder are multifactorial but are significantly increased in this post-surgical population. This study revealed a low treatment rate for attention-deficit/hyperactivity disorder, and a significant impact on the quality of life in these children.
Keywords: adolescent; aortic arch interruption; aortic coarctation; aortic arch surgery; article; attention deficit disorder; child; cross-sectional study; female; heart ventricle septum defect; human; hypoplastic left heart syndrome; major clinical study; male; newborn surgery; Norwood procedure; observational study; prevalence; quality of life; risk assessment; risk factor

Postoperative care of the adult with congenital heart disease - Maxwell, B.; Steppan, J. (Seminars in Cardiothoracic and Vascular Anesthesia, 2015)
An increasing number of children with congenital heart disease survive to adulthood, but many adults require surgical intervention and can present complex management challenges in the perioperative period. This review will address common considerations that surgeons, anesthesiologists, and intensivists are likely to face in caring for this growing population.
Keywords: air embolism; article; assisted circulation; Blalock Taussig shunt; cardiac patient; cardiac surgeon; comorbidity; congenital heart disease; echocardiography; Fontan procedure; heart arrhythmia; heart catheterization; heart right ventricle; heart single ventricle; intensivist; lung artery pressure; palliative therapy; postoperative care; preoperative evaluation; psychological aspect; pulmonary artery stenosis; reperfusion injury; right ventricle to pulmonary artery conduit; social aspect; surgeon

Use of a 1.0 Tesla open scanner for evaluation of pediatric and congenital heart disease: A retrospective cohort study - Lu, J.C.; Nielsen, J.C.; Morowitz, L.; Musani, M.; Ghadimi Mahani, M.; Agarwal, P.P.; Ibrahim, E.-S.H.; Dorfman, A.L. (Journal of Cardiovascular Magnetic Resonance, 2015)
Background: Open cardiovascular magnetic resonance (CMR) scanners offer the potential for imaging patients with claustrophobia or large body size, but at a lower 1.0 Tesla magnetic field. This study aimed to evaluate the efficacy of open CMR for evaluation of pediatric and congenital heart disease. Methods: This retrospective, cross-sectional study included all patients ≤18 years old or with congenital heart disease who underwent CMR on an open 1.0 Tesla scanner at two centers from 2012-2014. Indications for CMR and clinical questions were extracted from the medical record. Studies were qualitatively graded for image quality and diagnostic utility. In a subset of 25 patients, signal-to-noise (SNR) and contrast-to-noise (CNR) ratios were compared to size- and diagnosis-matched patients with CMR on a 1.5 Tesla scanner. Results: A total of 65 patients (median 17.3 years old, 60% male) were included. Congenital heart disease was present in 32 (50%), with tetralogy of Fallot and bicuspid aortic valve the most common diagnoses. Open CMR was used due to scheduling/equipment issues in 51 (80%), claustrophobia in 7 (11%), and patient size in 3 (5%); 4 patients with claustrophobia had failed CMR on a different scanner, but completed the study on open CMR without sedation. All patients had good or excellent image quality on black blood, phase contrast, magnetic resonance angiography, and late gadolinium enhancement imaging. There was below average image quality in 3/63 (5%) patients with cine images, and 4/15 (27%) patients with coronary artery imaging. SNR and CNR were decreased in cine and magnetic resonance angiography images compared to 1.5 Tesla. The clinical question was answered adequately in all but 2 patients; 1 patient with a Fontan had artifact from an embolization coil limiting RV volume analysis, and in 1 patient the right coronary artery origin was not well seen. Conclusions: Open 1.0 Tesla scanners can effectively evaluate pediatric and congenital heart disease, including patients with claustrophobia and larger body size. Despite minor artifacts and differences in SNR and CNR, the majority of clinical questions can be answered adequately, with some limitations with coronary artery imaging. Further evaluation is necessary to optimize protocols and image quality.
Keywords: gadolinium pentetate meglumine; gadoteridol; adolescent; adult; article; artifact; bicuspid aortic valve; cardiovascular magnetic resonance; childhood disease; claustrophobia; cohort analysis; congenital heart disease; contrast enhancement; contrast to noise ratio; controlled study; cross-sectional study; data extraction; diagnostic value; embolization coil; Fallot tetralogy; female; heart right ventricle volume; human; image quality; magnetic resonance angiography; major clinical study; male; medical record; nuclear magnetic resonance scanner; priority journal; qualitative analysis; retrospective study; right coronary artery; sedation; signal noise ratio; magnevist; prohance; 1.0 Tesla

Left Ventricular Remodeling and Function in Children with Biventricular Circulation After Fetal Aortic Valvuloplasty - Friedman, K.G.; Freud, L.; Escobar-Diaz, M.; Banka, P.; Emani, S.; Tworetzky, W. (Pediatric Cardiology, 2015)
Fetal aortic valvuloplasty (FAV) has shown promise in averting the progression of fetal aortic stenosis to hypoplastic left-heart syndrome. Altered loading conditions due to valvar disease, intrinsic endomyocardial abnormalities, and procedures that alter endomyocardial mechanics may place patients with biventricular circulation (BiV) after FAV at risk of abnormal LV remodeling and function. Using the most recent echo data on BiV patients after technically successful FAV (n = 34), we evaluated LV remodeling pattern, risk factors for pathologic LV remodeling, and the association between LV remodeling pattern and LV function. Median age at follow-up was 4.7 years (range 1.0–12.5). Cardiac interventions were common. At latest follow-up, no patient had hypoplastic LV. Nineteen patients (55 %) had dilated LV, and five (16 %) patients had severely dilated LV. LV remodeling patterns were as follows: 12 (35 %) normal ventricle, 11 (32 %) mixed hypertrophy, 8 (24 %) eccentric hypertrophy or remodeling, and 3 (9 %) concentric hypertrophy. Univariate factors associated with pathologic LV remodeling were long-standing AR, ≥2 cardiac interventions, EFE resection, and aortic or mitral regurgitation ≥ moderate at most recent follow-up. In multivariate analysis, only long-standing AR fraction remained associated with pathologic remodeling. Pathologic LV remodeling was associated with depressed ejection fraction, lower septal E´, and higher E/E´. Pathologic LV remodeling, primarily eccentric or mixed hypertrophy, is common in BiV patients after FAV and is related to LV loading conditions imposed by valvar disease. Pathologic remodeling is associated with both systolic and diastolic dysfunction in this population.
Keywords: aortic regurgitation; aortic valve replacement; aortic valve repair; article; biventricular circulation; cardiovascular risk; child; clinical article; cohort analysis; diastolic dysfunction; female; fetal aortic valvuloplasty; fetus; follow up; heart disease; heart left ventricle ejection fraction; heart left ventricle enddiastolic volume; heart left ventricle function; heart left ventricle hypertrophy; heart left ventricle mass; heart left ventricle volume; heart ventricle remodeling; human; hypoplastic left heart syndrome; male; mitral valve regurgitation

High-risk single ventricle palliation in children with Down syndrome: Single institution experience - Ooi, Y.K.; Sinha, P.; Gierdalski, M.; Harahsheh, A. (Cardiology in the Young, 2015)
Background: Of the children with Down syndrome 40-50% have cardiac defects and the majority of these cardiac defects are amenable to biventricular repair. The outcome of single ventricle palliation is improving; nonetheless, there are limited data on Down syndrome patients with associated high-risk factors undergoing single ventricle palliation. Our aim was to study the outcomes of children with Down syndrome and high-risk factors on the single ventricle palliation pathway. Methods: A retrospective study on all patients with Down syndrome on the single ventricle palliation pathway from 2005 until 2011 was conducted. Operative, clinical, echocardiographic, haemodynamic data, and follow-up data were reviewed. Results: A total of 310 patients underwent at least one single ventricle surgical intervention. Of those, eight patients had Down syndrome, five of which had associated risk factors - low birth weight, high pulmonary vascular resistance, pulmonary vein stenosis, significant atrioventricular valve regurgitation, and extracardiac anomalies. Mortality in the high-risk group was 80% (4/5), compared with 33% (1/3) in the non-high-risk patients. Overall, after a median follow-up period of 138 days (8-576 days), only 37.5% (3/8) of patients were alive. Conclusion: Despite many improvements in the care of single ventricle patients, the fate of those with Down syndrome and associated high-risk factors remains poor. Further multicentre longer-term studies are needed to validate and quantify the cumulative effects of negative prognostic factors in this complex group of patients.
Keywords: article; cardiovascular mortality; cardiovascular risk; child; Down syndrome; echocardiography; follow up; heart disease; heart hemodynamics; heart surgery; high risk patient; human; low birth weight; lung vascular resistance; major clinical study; mitral valve regurgitation; pulmonary vein obstruction; retrospective study; single ventricle palliation

Quality of life in pediatric patients affected by electrophysiologic disease - Czosek, R.J.; Cassedy, A.E.; Wray, J.; Wernovsky, G.; Newburger, J.W.; Mussatto, K.A.; Mahony, L.; Tanel, R.E.; Cohen, M.I.; Franklin, R.C.; Brown, K.L.; Rosenthal, D.; et al. (Heart Rhythm, 2015)
Background Treatment of electrophysiologic (EP) disease in pediatric patients has improved; however, the effects on quality of life (QOL) are unknown. Objective The purpose of this study was to compare QOL within EP disease groups and to other congenital heart diseases, to evaluate the effects of cardiac rhythm devices on QOL, and to identify drivers of QOL in EP disease. Methods Cross-sectional study of patient/parent proxy-reported Pediatric Cardiac Quality of Life Inventory scores (Total, Disease Impact, Psychosocial Impact) in subjects aged 8 to 18 years from 11 centers with congenital complete heart block (CCHB), ventricular tachycardia (VT), supraventricular tachycardia (SVT), and long QT syndrome (LQTS). QOL was compared between EP disease groups and congenital heart disease groups [bicuspid aortic valve (BAV), tetralogy of Fallot (TOF), and Fontan]. General linear modeling was used to perform group comparisons and to identify predictors of QOL variation. Results Among 288 patient-parent pairs, mean age was 12.8 ± 3.0 years. CCHB (μ = 83) showed higher patient Total QOL than other EP disease cohorts (P ≤.02; LQTS μ = 73; SVT μ = 74). SVT (μ = 75) and LQTS (μ = 75) had lower patient Total scores than BAV (μ = 81; P ≤.008). Patient/parent-proxy QOL scores for all EP disease groups were not different than TOF and higher than Fontan. The presence of a cardiac rhythm device was associated with lower QOL scores in LQTS (μ = 66 vs μ = 76; P <.01). Predictors of lower patient/parent-proxy QOL included EP disease type (P ≤.03), increased medical care utilization (P ≤.04), and no parental college degree (P ≤.001). Conclusion Given the significant variation in QOL in EP disease type, stratification by EP disease type and increased medical care utilization may allow for targeted interventions to improve QOL.
Keywords: adolescent; adult; article; bicuspid aortic valve; cardiovascular therapeutic device; catheter ablation; child; childhood disease; cohort analysis; comparative study; complete heart block; congenital heart disease; cross-sectional study; Fallot tetralogy; female; Fontan procedure; health care utilization; heart rhythm; heart ventricle tachycardia; human; long QT syndrome; major clinical study; male; multicenter study; priority journal; quality of life; secondary analysis; supraventricular tachycardia; validation study

American Academy of Pediatrics Section on Cardiology Meeting - Snyder, C.; Moodie, D. (Congenital Heart Disease, 2015)
Keywords: aortic dilation; article; artificial embolization; body mass; body surface; body weight; brain ventricle dilatation; cardiovascular response; central venous pressure; congenital heart disease; Down syndrome; echocardiography; electrocardiogram; Fontan procedure; Glenn shunt; heart dilatation; heart pacing; heart single ventricle; heart ventricle septum defect; hemodynamics; human; obesity; patent ductus arteriosus; physical examination; postoperative period; predictive value; preoperative period; pressure transducer; priority journal; screening test; sensitivity and specificity; survival rate; thorax radiography

Bronchoscopic guidance of endovascular stenting limits airway compression - Ebrahim, M.; Hagood, J.; Moore, J.; El-Said, H. (Catheterization and Cardiovascular Interventions, 2015)
Objective Bronchial compression as a result of pulmonary artery and aortic arch stenting may cause significant respiratory distress. We set out to limit airway narrowing by endovascular stenting, by using simultaneous flexible bronchoscopy and graduated balloon stent dilatation, or balloon angioplasty to determine maximum safe stent diameter. Methods Between August 2010 and August 2013, patients with suspected airway compression by adjacent vascular structures, underwent CT or a 3D rotational angiogram to evaluate the relationship between the airway and the blood vessels. If these studies showed close proximity of the stenosed vessel and the airway, simultaneous bronchoscopy and graduated stent re-dilation or graduated balloon angioplasty were performed. Results Five simultaneous bronchoscopy and interventional catheterization procedures were performed in four patients. Median age/weight was 33 (range 9-49) months and14 (range 7.6-24) kg, respectively. Three had hypoplastic left heart syndrome, and one had coarctation of the aorta (CoA). All had confirmed or suspected left main stem bronchial compression. In three procedures, serial balloon dilatation of a previously placed stent in the CoA was performed and bronchoscopy was used to determine the safest largest diameter. In the other two procedures, balloon testing with simultaneous bronchoscopy was performed to determine the stent size that would limit compression of the adjacent airway. In all cases, simultaneous bronchoscopy allowed selection of an ideal caliber of the stent that optimized vessel diameter while minimizing compression of the adjacent airway. Conclusion In cases at risk for airway compromise, flexible bronchoscopy is a useful tool to guide endovascular stenting. Maximum safe stent diameter can be determined without risking catastrophic airway compression.
Keywords: adult; aortic coarctation; article; balloon catheter; balloon dilatation; bronchial compression; bronchoscopy; bronchus obstruction; case report; child; computer assisted tomography; flexible bronchoscopy; human; hypoplastic left heart syndrome; male; pediatrics; percutaneous transluminal angioplasty; preschool child; pulmonary artery catheterization; vascular stent

Hybrid approach to the comprehensive stage II operation in a subset of single-ventricle variants - Decampli, W.M.; Fleishman, C.E.; Nykanen, D.G. (Journal of Thoracic and Cardiovascular Surgery, 2015)
Objective The objective of a hybrid approach to staged palliation of single-ventricle anomalies is designed to minimize the trauma of the first stage. However, the second stage is a complex procedure that may negate the advantages of the first stage. We sought to devise a "hybrid" approach to the second stage when aortic outflow is expected to remain unobstructed. Methods The procedure involves a simple incision into the main pulmonary artery, dilation/stenting of the ductal continuation, formation of a stented baffle between the branch pulmonary arteries' orifices, and a bidirectional Glenn connection. It avoids dissection of the distal arch and ductal continuation and obviates the need for a Damus-Kaye-Stansel connection. We carried out this procedure in 2 patients, one with unbalanced atrioventricular canal and the other with mitral atresia. Results Both patients underwent an uncomplicated operative procedure. Both patients were successfully weaned from the ventilator, with no clinically evident neurologic injury. The first patient died of complications related to thrombosis of the left pulmonary artery before initiation of anticoagulation. The second patient is alive and well 1 year postoperation with no obstruction to either systemic or pulmonary flow and no baffle leak and good right ventricle function. Conclusions This hybrid comprehensive stage II operation appears feasible and technically simpler than the conventional comprehensive stage II procedure. It is applicable to a subset of single-ventricle cases in which aortic outflow is anticipated to remain unobstructed. We recommend early postoperative anticoagulation to avoid early left pulmonary artery thrombosis.
Keywords: acetylsalicylic acid; enoxaparin; heparin; tissue plasminogen activator; anastomosis; anticoagulant therapy; aortic arch; aortic root; article; ascending aorta; atrioventricular canal; balloon catheter; balloon dilatation; bare metal stent; cardiac patient; cardiopulmonary bypass; case report; computed tomographic angiography; descending aorta; Down syndrome; echocardiography; extracorporeal oxygenation; femoral artery; heart catheterization; heart right ventricle function; heart single ventricle; heart surgery; heart ventricle enddiastolic pressure; human; incision; laparoscopic video camera; lung infection; mitral valve atresia; newborn; newborn disease; newborn surgery; peripheral artery stent; priority journal; pulmonary artery; radial artery; sternotomy; superior cava vein; surgical approach; systemic circulation; Opta Pro balloon; Palmaz Genesis 2510B; PG 1910B

Case studies of patients successfully and unsuccessfully managed pre- and post-fontan procedure - Ono, Y.; Mitsushita, N. (International Heart Journal, 2015)
As a result of advances and modifications in surgical procedures and the development of drugs for pulmonary arterial hypertension, many patients who have undergone Fontan procedures are able to enjoy good quality of life, without pulmonary arterial hypertension and severe complications. In Shizuoka Children’s Hospital, drugs for pulmonary arterial hypertension have long been given to Fontan candidates and patients with established Fontan circulation to maintain sufficient pulmonary blood flow and suppress pulmonary arterial hypertension. We present three typical cases that were treated with anti-pulmonary hypertensive drugs before or after Fontan procedure. The first case had asplenia syndrome, and a single ventricle with major aortopulmonary collateral arteries. Anti-pulmonary hypertensive therapy permitted a Fontan procedure and maintained a good long-term quality of life. The second case was a Down syndrome patient who had progressive cyanosis after a Fontan operation. Anti-pulmonary hypertensive therapy improved cyanosis. The third case suffered from protein-losing enteropathy, for which all procedures and medical therapies were ineffective. Fontan candidates and patients with Fontan circulation have varied anatomical backgrounds and pulmonary properties. We must identify the conditions that lead to successful Fontan procedure and Fontan circulation correction, as well as conditions that result in failed Fontan procedure and poorly-controlled Fontan circulation.
Keywords: beraprost; bosentan; sildenafil; angiography; aortopulmonary septal defect; artery reconstruction; article; asplenia; atrioventricular septal defect; case report; coronary artery collateral circulation; cyanosis; Down syndrome; Fontan procedure; Glenn shunt; heart catheterization; heart single ventricle; home oxygen therapy; human; infant; lung vein drainage anomaly; oxygen saturation; priority journal; protein losing gastroenteropathy; pulmonary hypertension; pulmonary valve atresia

Occult progressive pulmonary arterial occlusion associated with right ventricular hypertension in patients with systemic arteriopathy - Morray, B.H.; Bergersen, L.; Lock, J.E.; Marshall, A.C. (Congenital Heart Disease, 2015)
Objectives: Peripheral pulmonary artery stenosis (PPS) is a heterogeneous disease associated with numerous clinical or syndromic disorders including Williams syndrome. Previous studies focusing on patients with Williams syndrome have documented spontaneous improvement in branch pulmonary artery (PA) stenosis and right ventricular pressure. The goal of this study is to identify angiographic evidence of spontaneous occlusion or loss of segmental PAs in patients with PPS. Methods: Patients undergoing serial catheterization for PPS at Boston Children's Hospital between 1999 and 2014 were selected. Patients with structural heart disease such as tetralogy of Fallot, truncus arteriosus, transposition of the great arteries, or single ventricle were excluded. Hemodynamic data were extracted from catheterization reports, all available angiograms were reviewed, and evidence of segmental PA loss was documented based on defined angiographic criteria. Results: Forty-two patients were included in the study. Each patient underwent an average of 5 catheterizations over the 15-year study period. The average RV pressure at initial catheterization was near systemic levels. Evidence of segmental PA loss was present in 40% of patients. Almost 30% of patients with vessel loss demonstrated loss at their initial catheterization, and 65% of patients experienced loss of multiple vessels over time. Patients with vessel loss tended to be older at initial catheterization and have higher average RV pressures at their most recent catheterization than those without vessel loss. Conclusions: Progressive segmental PA loss in patients with systemic arteriopathy and PPS has not been well described previously. In this cohort, segmental PA loss occurred in 40% of patients, resulting in persistently elevated PA pressures relative to patients who did not develop vessel loss. These findings highlight the importance of surveillance in this population of patients with systemic arteriopathy and severe PPS.
Keywords: adolescent; Alagille syndrome; angiography; aortic stenosis; artery disease; article; child; clinical article; disease association; familial disease; female; heart right ventricle hypertension; heart right ventricle pressure; hemodynamics; human; hypertension; male; moyamoya disease; outcome assessment; peripheral pulmonary artery stenosis; priority journal; pulmonary artery catheterization; pulmonary artery stenosis; retrospective study; systemic arteriopathy; venous return; Williams Beuren syndrome

Effect of maternal diabetes on the embryo, fetus, and children: Congenital anomalies, genetic and epigenetic changes and developmental outcomes - Ornoy, A.; Reece, E.A.; Pavlinkova, G.; Kappen, C.; Miller, R.K. (Birth Defects Research Part C - Embryo Today: Reviews, 2015)
Introduction: Pregestational and gestational diabetes mellitus (PGDM; GDM) are significant health concerns because they are associated with an increased rate of malformations and maternal health complications. Methods: We reviewed the data that help us to understand the effects of diabetes in pregnancy. Results: Diabetic embryopathy can affect any developing organ system, but cardiovascular and neural tube defects are among the most frequent anomalies. Other complications include preeclampsia, preterm delivery, fetal growth abnormalities, and perinatal mortality. Neurodevelopmental studies on offspring of mothers with diabetes demonstrated increased rate of Gross and Fine motor abnormalities, of Attention Deficit Hyperactivity Disorder, learning difficulties, and possibly also Autism Spectrum Disorder. The mechanisms underlying the effects of maternal hyperglycemia on the developing fetus may involve increased oxidative stress, hypoxia, apoptosis, and epigenetic changes. Evidence for epigenetic changes are the following: not all progeny are affected and not to the same extent; maternal diet may influence pregnancy outcomes; and maternal diabetes alters embryonic transcriptional profiles and increases the variation between transcriptomic profiles as a result of altered gene regulation. Research in animal models has revealed that maternal hyperglycemia is a teratogen, and has helped uncover potential therapeutic targets which, when blocked, can mitigate or ameliorate the negative effects of diabetes on the developing fetus. Conclusions: Tight metabolic control, surveillance, and labor management remain the cornerstone of care for pregnant women with diabetes, but advances in the field indicate that new treatments to protect the mother and baby are not far from becoming clinical realities.
Keywords: adiponectin; ghrelin; glucose; leptin; acrania; anencephalus; apoptosis; arrhinencephaly; article; attention deficit disorder; autism; brain malformation; breast feeding; cardiovascular disease; cataract; chromatin assembly and disassembly; cleft lip; cleft palate; cognitive defect; congenital malformation; craniofacial malformation; embryopathy; epigenetics; exencephaly; Fallot tetralogy; fetus growth; follow up; frontal nasal dysplasia; gene expression; great vessels transposition; growth disorder; heart left ventricle double outlet; heart right ventricle double outlet; hemifacial microsomia; heredity; holoprosencephaly; human; hyperglycemia; hypoplastic left heart syndrome; hypoxia; intrauterine growth retardation; learning disorder; low birth weight; macrosomia; maternal diabetes mellitus; meningomyelocele; metabolic disorder; microcephaly; micrognathia; microophthalmia; microtia; mitral valve atresia; motor dysfunction; neural tube defect; neurologic disease; nutrition; oxidative stress; perinatal mortality; postnatal growth; preeclampsia; pregnancy complication; pregnancy outcome; premature labor; prevention; priority journal; spinal dysraphism; transcription regulation; tricuspid valve atresia

Sports participation and quality of life in adolescents and young adults with congenital heart disease - Dean, P.N.; Gillespie, C.W.; Greene, E.A.; Pearson, G.D.; Robb, A.S.; Berul, C.I.; Kaltman, J.R. (Congenital Heart Disease, 2015)
Background: Adolescents and young adults with congenital heart disease (CHD) are often restricted from physical activity and sports participation, which may have adverse effects. Objectives: To determine the amount of physical activity, type of sports participation, and reasons for sports restrictions, and to evaluate the effect of sports participation on quality of life (QoL) in a cohort of patients with CHD. Methods: Individuals with CHD aged 13-30 years were recruited at outpatient visits or via mailings. They completed a questionnaire addressing physical activity, sports participation, sports restrictions, and QoL (Pediatric Quality of Life Inventory). We also reviewed the patient's medical record. Results: Of the 177 patients who responded (mean age 20 years), 31% have mild CHD, 40% have moderate CHD, and 29% have severe CHD. In the cohort, 52% participate in competitive sports, 25% recreational sports, and 23% no sports. Among patients with severe CHD, 29% participate in competitive sports that would be restricted by published guidelines (36th Bethesda Conference). After controlling for age, sex, CHD severity, residual hemodynamic disease, and comorbidities, participation in competitive sports and increased frequency of physical activity are independently associated with a higher QoL (P = .003 and P = .001, respectively). In an identical model, competitive sports participation and frequency of physical activity are associated with higher maximum predicted oxygen consumption (VO2) (n = 40; P = .002 and .02) and slightly lower body mass index (BMI) (P = .02 and .01). All findings were similar when analyses were stratified by recruitment method. Conclusions: Patients with CHD commonly participate in competitive sports, and such participation is associated with higher QoL, improved exercise capacity, and lower BMI.
Keywords: adolescent; adult; article; assessment of humans; body mass; cohort analysis; congenital heart disease; disease severity; female; Fontan procedure; human; major clinical study; male; medical record review; outpatient; oxygen consumption; Pediatric Quality of Life Inventory; physical activity; practice guideline; prediction; priority journal; quality of life; sedentary lifestyle; sport

Caregiver anxiety due to interstage feeding concerns - Stewart, J.; Dempster, R.; Allen, R.; Miller-Tate, H.; Dickson, G.; Fichtner, S.; Principe, A.J.; Fonseca, R.; Nicholson, L.; Cua, C.L. (Congenital Heart Disease, 2015)
Introduction: Improved weight gain during the interstage (IS) period has been shown to improve overall outcomes in patients with single ventricle physiology (SVP). This emphasis on nutrition may have untoward effects, such as increasing anxiety/stress levels in caregivers, who are already known to be at risk for increased anxiety/stress levels. The goal of this study was to evaluate anxiety/stress levels of caregivers as it pertains to feeding during the IS period and to determine if certain characteristics were associated with higher anxiety/stress scores. Methods: Caregivers of children with SVP who completed the IS period, defined as the time between the first and second cardiac surgeries, were recruited. Baseline demographics were obtained. Anxiety/stress levels were measured via eight questions using a 0- to 10-point scale. Correlations were performed between demographic variables and anxiety/stress level scores. Results: Fifty-six surveys were completed (39 males, 27 females) on 43 children. Fourteen children required tube feeds during the IS period. There were significant correlations between anxiety/stress scores and caregiver's gender, caregiver's age, caregiver's level of education, percent of time a caregiver spent feeding the child, if caregivers were taking medications for anxiety, and if the child was seen in the emergency room during the IS period. There were no correlation of anxiety/stress scores with caregiver's race, child's underlying cardiac diagnosis, age of child, route of feeding during the IS period, birth order of the child or number of children in the family, relationship status, or distance from the hospital. Conclusion: In general, caregivers of children with SVP experience anxiety/stress during the IS period specifically due to feeding concerns. Certain intrinsic and extrinsic characteristics were associated with higher anxiety/stress levels. Future studies are needed to determine how to minimize anxiety/stress levels during this stressful time period.
Keywords: antidepressant agent; anxiolytic agent; adult; age; anxiety; anxiety disorder; article; birth order; bottle feeding; caregiver; child nutrition; cross-sectional study; depression; educational status; enteric feeding; family size; father; feeding; female; food intake; health care survey; heart single ventricle; heart surgery; hospital discharge; human; interstage period; major clinical study; male; mother; nasogastric tube; nose feeding; postoperative period; priority journal; prospective study; sex difference; stomach tube; time; body weight gain

Unsatisfactory Early and Late Outcomes After Fontan Surgery Delayed to Adolescence and Adulthood - Forsdick, V.; Iyengar, A.J.; Carins, T.; Gentles, T.L.; Weintraub, R.G.; Celermajer, D.S.; d'Udekem, Y. (Seminars in Thoracic and Cardiovascular Surgery, 2015)
The ideal age to perform the Fontan procedure is still unknown. The aim of this study is to determine outcomes after Fontan surgery delayed to adolescence and adulthood in Australia and New Zealand. Patients who had undergone a Fontan procedure at 15 years of age or older were identified in the 1133 patients registered in the Australia and New Zealand Fontan Registry until December 2012. A total of 45 patients underwent the following Fontan procedure at a median age of 18.3 years (16-21 years): 24 atriopulmonary connections, 10 lateral tunnel, and 11 extracardiac conduits. Hospital mortality was 13% (6 of 45). After a mean follow-up of 15.5 ± 9 years, there were 8 late deaths. Survival rates after 10, 20, and 25 years were 79% (95% CI: 64-89), 70% (95% CI: 51-83), and 70% (95% CI: 51-83), respectively. Freedom from Fontan failure (death, heart transplantation, Fontan takedown, protein-losing enteropathy, and poor functional status) after 10 and 20 years was 63% (95% CI: 47-76) and 35% (95% CI: 19-52), respectively. Patients with a single left ventricle had a lower risk of failure (hazard ratio = 0.25, 95% CI: 0.10-0.59; P = 0.002). Arrhythmias developed in 29 patients after a median of 0.1 years (0-9.3 years) and 10 required a permanent pacemaker. Freedom from all adverse events at 10 years was 30% (95% CI: 16-45). Outcomes of the Fontan procedure in adolescents and adults are poor, with disproportionately high hospital mortality and late adverse events. The Fontan procedure should not be delayed to adolescence and adulthood and should be performed electively in childhood.
Keywords: adolescence; adolescent; adult; adulthood; article; Australia; Budd Chiari syndrome; cerebrovascular accident; complete heart block; congenital heart disease; controlled study; female; femoral vein; follow up; Fontan procedure; functional status; heart arrhythmia; heart muscle ischemia; heart transplantation; heart ventricle fibrillation; heart ventricle tachycardia; human; lung embolism; major clinical study; male; New Zealand; patient satisfaction; post treatment survival; prospective study; protein losing gastroenteropathy; supraventricular tachycardia; surgical mortality; thromboembolism; treatment failure; treatment outcome; vein thrombosis

Intratracheal heparin improves plastic bronchitis due to sulfur mustard analog - Houin, P.R.; Veress, L.A.; Rancourt, R.C.; Hendry-Hofer, T.B.; Loader, J.E.; Rioux, J.S.; Garlick, R.B.; White, C.W. (Pediatric Pulmonology, 2015)
Background: Inhalation of sulfur mustard (SM) and SM analog, 2-chloroethyl ethyl sulfide (CEES), cause fibrinous cast formation that occludes the conducting airways, similar to children with Fontan physiology-induced plastic bronchitis. These airway casts cause significant mortality and morbidity, including hypoxemia and respiratory distress. Our hypothesis was that intratracheal heparin, a highly cost effective and easily preserved rescue therapy, could reverse morbidity and mortality induced by bronchial cast formation. Methods: Sprague-Dawley rats were exposed to 7.5% CEES via nose-only aerosol inhalation to produce extensive cast formation and mortality. The rats were distributed into three groups: non-treated, phosphate-buffered saline (PBS)-treated, and heparin-treated groups. Morbidity was assessed with oxygen saturations and clinical distress. Blood and bronchoalveolar lavage fluid (BALF) were obtained for analysis, and lungs were fixed for airway microdissection to quantify the extent of airway cast formation. Results: Heparin, given intratracheally, improved survival (100%) when compared to non-treated (75%) and PBS-treated (90%) controls. Heparin-treated rats also had improved oxygen saturations, clinical distress and airway cast scores. Heparin-treated rats had increased thrombin clotting times, factor Xa inhibition and activated partial thromboplastin times, indicating systemic absorption of heparin. There were also increased red blood cells (RBCs) in the BALF in 2/6 heparin-treated rats compared to PBS-treated control rats. Conclusions: Intratracheal heparin 1 hr after CEES inhalation improved survival, oxygenation, airway obstruction, and clinical distress. There was systemic absorption of heparin in rats treated intratracheally. Some rats had increased RBCs in BALF, suggesting a potential for intrapulmonary bleeding if used chronically after SM inhalation.
Keywords: 2 chloroethyl ethyl sulfide; blood clotting factor 10a; heparin; mustard gas; mustard gas derivative; phosphate buffered saline; unclassified drug; aerosol; animal experiment; animal model; animal tissue; article; blood analysis; bronchitis; controlled study; cost effectiveness analysis; drug absorption; erythrocyte; hypoxemia; lung lavage; male; microdissection; morbidity; mortality; nonhuman; oxygen saturation; partial thromboplastin time; plastic bronchitis; priority journal; rat; Sprague Dawley rat; survival; thrombin time

Survival data and predictors of functional outcome an average of 15years after the fontan procedure: The pediatric heart network fontan cohort - Atz, A.M.; Zak, V.; Mahony, L.; Uzark, K.; Shrader, P.; Gallagher, D.; Paridon, S.M.; Williams, R.V.; Breitbart, R.E.; Colan, S.D.; Kaltman, J.R.; Margossian, R.; et al. (Congenital Heart Disease, 2015)
Objective: Multicenter longitudinal outcome data for Fontan patients surviving into adulthood are lacking. The aim of this study was to better understand contemporary outcomes in Fontan survivors by collecting follow-up data in a previously well-characterized cohort. Design: Baseline data from the Fontan Cross-Sectional Study (Fontan 1) were previously obtained in 546 Fontan survivors aged 11.9 ± 3.4years. We assessed current transplant-free survival status in all subjects 6.8 ± 0.4years after the Fontan 1 study. Anatomic, clinical, and surgical data were collected along with socioeconomic status and access to health care. Results: Thirty subjects (5%) died or underwent transplantation since Fontan 1. Subjects with both an elevated (>21pg/mL) brain natriuretic peptide and a low Child Health Questionnaire physical summary score (<44) measured at Fontan 1 were significantly more likely to die or undergo transplant than the remainder, with a hazard ratio of 6.2 (2.9-13.5). Among 516 Fontan survivors, 427 (83%) enrolled in this follow-up study (Fontan 2) at 18.4 ± 3.4years of age. Although mean scores on functional health status questionnaires were lower than the general population, individual scores were within the normal range in 78% and 88% of subjects for the Child Health Questionnaire physical and psychosocial summary score, and 97% and 91% for the SF-36 physical and mental aggregate score, respectively. Since Fontan surgery, 119 (28%) had additional cardiac surgery; 55% of these (n = 66) in the interim between Fontan 1 and Fontan 2. A catheter intervention occurred in 242 (57%); 32% of these (n = 78) after Fontan 1. Arrhythmia requiring treatment developed in 118 (28%) after Fontan surgery; 58% of these (n = 68) since Fontan 1. Conclusions: We found 95% interim transplant-free survival for Fontan survivors over an average of 7years of follow-up. Continued longitudinal investigation into adulthood is necessary to better understand the determinants of long-term outcomes and to improve functional health status.
Keywords: brain natriuretic peptide; dipeptidyl carboxypeptidase inhibitor; adult; article; catheter; cross-sectional study; follow up; Fontan procedure; health care access; health status; heart arrhythmia; heart surgery; heart transplantation; human; major clinical study; medical record review; priority journal; protein losing gastroenteropathy; questionnaire; Short Form 36; social status; survival; treatment outcome

Early Results of Neurodevelopment Following Hybrid Stage I for Hypoplastic Left Heart Syndrome - Cheatham, S.L.; Carey, H.; Chisolm, J.L.; Heathcock, J.C.; Steward, D. (Pediatric Cardiology, 2015)
Motor skills and neurodevelopment in infants with hypoplastic left heart syndrome (HLHS) who have undergone Hybrid Stage I palliation is unknown. The purpose of this study is to assess early neurodevelopment in infants with HLHS after Hybrid Stage I palliation. Developmental assessment was performed in HLHS infants who underwent Hybrid Stage I palliation at 2 and 4 months of age using the Test of Infant Motor Performance, and at 6 months of age, prior to undergoing the second staged surgery, using the Bayley Scales of Infant and Toddler Development, 3rd edition (Bayley-III). Results were compared to healthy control subjects and norm-referenced data. The HLHS group scored between −1 and −2 standard deviations (SD) below the mean at 2 months of age (p = 0.002), and within −1 SD of the mean, at 4 months of age (p = 0.0019), on the TIMP. Compared to the control group, composite motor skills were significantly lower at 6 months of age on the Bayley-III in the HLHS group (p = 0.0489), however, not significant for cognitive (p = 0.29) or language (p = 0.68). Percentile rank motor scores were 17 ± 20 % in the HLHS group compared to 85 ± 12 % for the healthy age-matched control group. Infants with HLHS who undergo Hybrid Stage I palliation score lower on standardized motor skill tests compared to healthy age-matched controls and the norm-referenced population. This suggests that infants with HLHS have poorer motor skill performance than typically developing infants at 6 months of age.
Keywords: tissue inhibitor of metalloproteinase; article; Bayley Scales of Infant Development; clinical article; cognitive development; controlled study; follow up; heart arrest; heart catheterization; human; hybrid stage I palliation; hypoplastic left heart syndrome; infant; language; mental development assessment; motor performance; nerve cell differentiation; outcome assessment; palliative therapy; treatment outcome

Children After Fontan have Strength and Body Composition Similar to Healthy Peers and Can Successfully Participate in Daily Moderate-to-Vigorous Physical Activity - Longmuir, P.E.; Corey, M.; Faulkner, G.; Russell, J.L.; McCrindle, B.W. (Pediatric Cardiology, 2015)
The objective of this study was to evaluate the active lifestyle capacity (daily physical activity, strength, flexibility, body composition) of children after the Fontan procedure; hypothesized to be lower than healthy peers. Participants (n = 64, 25 females) were 9.0 ± 1.7 years of age (range 6.0–11.7 years). Fontan completion occurred at 3.3 ± 1.4 years of age (5.7 ± 2.0 years prior). Canadian Health Measures Survey protocols assessed aerobic endurance (paced walking up/down steps), strength (handgrip), flexibility (sit and reach), body composition (body mass index), and daily moderate-to-vigorous physical activity (7-day accelerometry). Difference scores compared participant data to published norms (t tests). Linear regression evaluated age/gender/demographic factor associations. Children after Fontan had strength scores similar (mean difference 1.1 kg) to their peers were less likely to be obese (mean difference of body mass index = 1.1 ± 2.5, p = 0.001) and performed 50 min of moderate-to-vigorous activity (MVPA) per day (12 ± 17 min/day below healthy peers, p < 0.001). Estimated peak endurance (61 % of expected) and flexibility (64 % of expected) were lower than peers (p < 0.001). Almost all (60/63) participants demonstrated the capacity to perform at least 20 min of MVPA per day. Difference from norms was smaller among children younger at Fontan completion (4 ± 2 min/year) and taking antithrombotic medication (7 ± 18 and 22 ± 17 min/day for taking/not taking, respectively). Children after Fontan demonstrate the capacity for the daily physical activity associated with optimal health. They have similar strength and good body composition. We recommend that children after Fontan be counselled that they can successfully participate in healthy, active lifestyles and physically active peer play.
Keywords: anticoagulant agent; accelerometry; article; body composition; body mass; Canadian; child; controlled study; endurance; exercise; female; Fontan procedure; hand grip; heart ventricle function; human; lifestyle; major clinical study; male; outcome assessment; oxygen consumption; physical activity; rural area; strength; tricuspid valve atresia

Utility of a Dedicated Pediatric Cardiac Anticoagulation Program: The Boston Children’s Hospital Experience - Murray, J.M.; Hellinger, A.; Dionne, R.; Brown, L.; Galvin, R.; Griggs, S.; Mittler, K.; Harney, K.; Manzi, S.; VanderPluym, C.; Baker, A.; O’Brien, P.; et al. (Pediatric Cardiology, 2015)
Congenital heart disease is the leading cause of stroke in children. Warfarin therapy can be difficult to manage safely in this population because of its narrow therapeutic index, multiple drug and dietary interactions, small patient size, high-risk cardiac indications, and lack of data to support anticoagulation recommendations. We sought to describe our institution’s effort to develop a dedicated cardiac anticoagulation service to address the special needs of this population and to review the literature. In 2009, in response to Joint Commission National Patient Safety Goals for Anticoagulation, Boston Children’s Hospital created a dedicated pediatric Cardiac Anticoagulation Monitoring Program (CAMP). The primary purpose was to provide centralized management of outpatient anticoagulation to cardiac patients, to serve as a disease-specific resource to families and providers, and to devise strategies to evolve clinical care with rapidly emerging trends in anticoagulation care. Over 5 years the CAMP Service, staffed by a primary pediatric cardiology attending, a full-time nurse practitioner, and administrative assistant with dedicated support from pharmacy and nutrition, has enrolled over 240 patients ranging in age from 5 months to 55 years. The most common indications include a prosthetic valve (34 %), Fontan prophylaxis (20 %), atrial arrhythmias (11 %), cardiomyopathy (10 %), Kawasaki disease (7 %), and a ventricular assist device (2 %). A patient-centered multi-disciplinary cardiac anticoagulation clinic was created in 2012. Overall program international normalized ratio (INR) time in therapeutic range (TTR) is favorable at 67 % (81 % with a 0.2 margin) and has improved steadily over 5 years. Pediatric-specific guidelines for VKOR1 and CYP2C9 pharmacogenomics testing, procedural bridging with enoxaparin, novel anticoagulant use, and quality metrics have been developed. Program satisfaction is rated highly among families and providers. A dedicated pediatric cardiac anticoagulation program offers a safe and effective strategy to standardize anticoagulation care for pediatric cardiology patients, is associated with high patient and provider satisfaction, and is capable of evolving care strategies with emerging trends in anticoagulation.
Keywords: cytochrome P450 2C9; enoxaparin; anticoagulation; article; cardiac patient; cardiomyopathy; child; child health care; clinical medicine; dedicated pediatric vardiac anticoagulation program; health care utilization; health program; heart atrium arrhythmia; heart valve prosthesis; human; international normalized ratio; mucocutaneous lymph node syndrome; nurse practitioner; nutrition; outpatient care; patient satisfaction; pediatric cardiology; pediatric hospital; pharmacogenomics; practice guideline; program development; standardization; United States; ventricular assist device

Racial/ethnic differences in survival of United States children with birth defects: A population-based study - Wang, Y.; Liu, G.; Canfield, M.A.; Mai, C.T.; Gilboa, S.M.; Meyer, R.E.; Anderka, M.; Copeland, G.E.; Kucik, J.E.; Nembhard, W.N.; Kirby, R.S. (Journal of Pediatrics, 2015)
Objectives To examine racial/ethnic-specific survival of children with major birth defects in the US. Study design We pooled data on live births delivered during 1999-2007 with any of 21 birth defects from 12 population-based birth defects surveillance programs. We used the Kaplan-Meier method to calculate cumulative survival probabilities and Cox proportional hazards models to estimate mortality risk. Results For most birth defects, there were small-to-moderate differences in neonatal (<28 days) survival among racial/ethnic groups. However, compared with children born to non-Hispanic white mothers, postneonatal infant (28 days to <1 year) mortality risk was significantly greater among children born to non-Hispanic black mothers for 13 of 21 defects (hazard ratios [HRs] 1.3-2.8) and among children born to Hispanic mothers for 10 of 21 defects (HRs 1.3-1.7). Compared with children born to non-Hispanic white mothers, a significantly increased childhood (≤8 years) mortality risk was found among children born to Asian/Pacific Islander mothers for encephalocele (HR 2.6), tetralogy of Fallot, and atrioventricular septal defect (HRs 1.6-1.8) and among children born to American Indian/ Alaska Native mothers for encephalocele (HR 2.8), whereas a significantly decreased childhood mortality risk was found among children born to Asian/Pacific Islander mothers for cleft lip with or without cleft palate (HR 0.6). Conclusion Children with birth defects born to non-Hispanic black and Hispanic mothers carry a greater risk of mortality well into childhood, especially children with congenital heart defect. Understanding survival differences among racial/ethnic groups provides important information for policy development and service planning.
Keywords: Alaska Native; American Indian; anencephalus; aortic coarctation; aortic valve stenosis; arm malformation; article; Asian; atrioventricular septal defect; child; childhood mortality; cleft lip; cleft palate; congenital malformation; diaphragm hernia; Down syndrome; encephalocele; esophagus atresia; ethnic difference; Fallot tetralogy; gastroschisis; Hispanic; human; hypoplastic left heart syndrome; infant mortality; intestine atresia; leg malformation; live birth; major clinical study; newborn mortality; omphalocele; overall survival; Pacific Islander; population research; priority journal; pylorus stenosis; race difference; spinal dysraphism; survival; survival rate; tracheoesophageal fistula; United States

Physical and neurodevelopmental outcomes in children with single-ventricle circulation - Davidson, J.; Gringras, P.; Fairhurst, C.; Simpson, J. (Archives of Disease in Childhood, 2015)
Objective: To investigate longer-term physical and neurodevelopmental outcomes of patients with hypoplastic left heart syndrome (HLHS) compared with other patients with functionally single-ventricle circulation surviving beyond the age of 10 years. Design: A retrospective, observational study from a UK tertiary centre for paediatric cardiology. Results: 58 patients with HLHS and 44 non-HLHS patients with single-ventricle physiology were included. Subjective reduction in exercise tolerance was reported in 72% (95% CI 61% to 84%) of patients with HLHS and 45% (31% to 60%) non-HLHS patients. Compared with non-HLHS patients, educational concerns were reported more frequently in patients with HLHS, 41% (29% to 54%) vs 23% (10% to 35%), as was a diagnosis of a behaviour disorder (autism or attention deficit hyperactivity disorder) 12% (4% to 21%) vs 0%, and referral to other specialist services 67% (55% to 79%) vs 48% (33% to 63%). Conclusions: Within a group of young people with complex congenital heart disease, those with HLHS are likely to have worse physical, psychological and educational outcomes.
Keywords: adolescent; article; attention deficit disorder; autism; cardiopulmonary exercise test; child; controlled study; exercise tolerance; female; heart single ventricle; human; hypoplastic left heart syndrome; major clinical study; male; observational study; outcome assessment; pediatric cardiology; priority journal; retrospective study; United Kingdom

Prenatally diagnosed neck masses: Long-term outcomes and quality of life - Sheikh, F.; Akinkuotu, A.; Olutoye, O.O.; Pimpalwar, S.; Cassady, C.I.; Fernandes, C.J.; Ruano, R.; Lee, T.C.; Cass, D.L. (Journal of Pediatric Surgery, 2015)
Purpose To determine long-term outcomes of fetuses with neck masses (NM), including functional and cosmetic results. Methods A retrospective review was performed of all fetuses evaluated for NM from November 2001 to March 2014. Quality of life (QOL) was evaluated using the validated PedsQL™ questionnaire. Results Of 35 fetuses evaluated, 9 died perinatally and 1 died late from tracheostomy complications. NM ranged from 4 to 20 cm (mean, 9.1 cm); 18 were delivered by EXIT. Of 25 surviving patients, 22 had mass resection, 7 requiring more than one procedure. Surviving patients with lymphatic malformations (LM) had the highest incidence of moderate and severe disfigurement and a higher rate of persistent/recurrent disease (100% vs. 31%, p = 0.002) and cranial nerve dysfunction (50% vs. 0%, p = 0.005) compared to those with non-LM diagnoses. Of 9 children attending school, 78% achieve grades of A/B's. QOL for 13 patients revealed a mean score of 83/100 for physical and 78/100 for psychosocial functioning. Median follow-up was 6 years (7 months-17 years). Conclusion Unlike those with teratoma or other lesions, children with congenital cervicofacial LM are at high-risk for persistent disease, nerve dysfunction and moderate-severe disfigurement. There is substantial perinatal morbidity for fetuses with neck masses, but for those surviving, the long-term functional and cognitive outcomes are good.
Keywords: airway obstruction; article; clinical article; controlled study; fetus; fetus heart; follow up; gestational age; great vessels transposition; heart failure; hemangioendothelioma; human; hypoplastic left heart syndrome; long term care; lymphatic malformation; male; neck tumor; premature labor; prenatal diagnosis; priority journal; quality of life; questionnaire; recurrent disease; retrospective study; sclerotherapy; teratoma; thymus cyst; vocal cord disorder

Pediatric heart transplantation - Schweiger, M.; Stiasny, B.; Dave, H.; Cavigelli-Brunner, A.; Balmer, C.; Kretschmar, O.; Bürki, C.; Klauwer, D.; Hübler, M. (Journal of Thoracic Disease, 2015)
Pediatric heart transplantation (pHTx) represents a small (14%) but very important and particular part in the field of cardiac transplantation. This treatment has lifelong impact on children. To achieve the best short and especially long-term survival with adequate quality of life, which is of crucial importance for this young patient population, one has to realize and understand the differences with adult HTx. Indication for transplantation, waitlist management including ABO incompatible (ABOi) transplantation and immunosuppression differ. Although young transplant recipients are ultimately likely to be considered for re-transplantation. One has to distinguish between myopathy and complex congenital heart disease (CHD). The differences in anatomy and physiology make the surgical procedure much more complex and create unique challenges. These recipients need a well-organized and educated team with pediatric cardiologists and intensivists, including a high skilled surgeon, which is dedicated to pHTx. Therefore, these types of transplants are best concentrated in specialized centers to achieve promising outcome.
Keywords: inotropic agent; article; blood group ABO incompatibility; cardiac allograft vasculopathy; cardiomyopathy; congenital heart disease; donor selection; Fontan procedure; geographic distribution; graft recipient; heart failure; heart transplantation; high risk population; human; life expectancy; long term care; morbidity; mortality; Norwood procedure; patient selection; pediatrics; practice guideline; psychosocial care; resuscitation; risk factor; surgical technique; survival rate; treatment contraindication; ventricular assist device

Supporting families in neonatal loss: relationship and faith key to comfort - Holston, J.T. (Journal of Christian nursing : a quarterly publication of Nurses Christian Fellowship, 2015)
Around 20,000 neonatal deaths occur each year, many from congenital heart defects such as hypoplastic left heart syndrome. Nurses are on the frontline of caring for families experiencing neonatal loss. Careful spiritual and cultural assessment, attention to beliefs, focusing on relationship, and helping families create legacy can assist with grieving and making meaning out of loss.
Keywords: bereavement; case report; child death; Christianity; decision making; empathy; family; female; grief; health personnel attitude; human; hypoplastic left heart syndrome; infant; male; newborn; newborn intensive care; nurse attitude; nursing; nursing staff; psychology; terminal care

Immune Abnormalities in Fontan Protein-Losing Enteropathy: A Case-Control Study - Magdo, H.S.; Stillwell, T.L.; Greenhawt, M.J.; Stringer, K.A.; Yu, S.; Fifer, C.G.; Russell, M.W.; Schumacher, K.R. (Journal of Pediatrics, 2015)
Objective To comprehensively characterize the immunologic characteristics of patients with protein-losing enteropathy (PLE) post-Fontan and compare them with patients without PLE post-Fontan. Study design Patients with PLE post-Fontan and age-matched controls post-Fontan were prospectively studied with laboratory markers of immune function. Infectious history was obtained by interview and chart review. The groups' demographics, cardiac history, immune characteristics, and infection history were compared using appropriate 2-group statistics. Results A total of 16 patients enrolled (8 patients with PLE and 8 controls). All patients with PLE had lymphopenia compared with 25% of controls (P =.01). All patients with PLE had markedly depressed CD4 T cell counts (median 58 cells/μL) compared with controls (median 450 cells/μL, P =.0002); CD4% was also low in the PLE group (12.3%) and normal in control (36.9%, P =.004). Both groups had mildly depressed CD8 T cells and normal to slightly elevated natural killer and B-cell subsets. A majority of patients with PLE (62.5%) had negative titers to measles, mumps, and rubella vaccination, compared with no control Fontan with a negative titer (P =.03). Despite profoundly low CD4 counts, the frequency of infection was not different between groups with no reported opportunistic infections. Conclusions Patients with Fontan-associated PLE have extensive quantitative immune abnormalities, particularly CD4 deficiency. These immune abnormalities are similar to those found in non-Fontan patients with PLE caused by intestinal lymphangiectasia.
Keywords: biological marker; immunoglobulin A; immunoglobulin G; immunoglobulin G1; immunoglobulin G2; immunoglobulin G3; immunoglobulin M; article; autoimmune disease; B lymphocyte; case control study; CD4 lymphocyte count; CD8+ T lymphocyte; child; clinical article; controlled study; demography; female; Fontan procedure; human; immunoglobulin blood level; immunological procedures; interview; intestine lymphangiectasia; lymphocyte subpopulation; lymphocytopenia; male; measles; mumps; natural killer cell; opportunistic infection; postoperative period; preschool child; priority journal; prospective study; protein losing gastroenteropathy; rubella; vaccination

Implementation of the American College of Cardiology/American Heart Association 2008 Guidelines for the Management of Adults with Congenital Heart Disease - Goossens, E.; Fernandes, S.M.; Landzberg, M.J.; Moons, P. (American Journal of Cardiology, 2015)
Although different guidelines on adult congenital heart disease (ACHD) care advocate for lifetime cardiac follow-up, a critical appraisal of the guideline implementation is lacking. We investigated the implementation of the American College of Cardiology/American Heart Association 2008 guidelines for ACHD follow-up by investigating the type of health care professional, care setting, and frequency of outpatient visits in young adults with CHD. Furthermore, correlates for care in line with the recommendations or untraceability were investigated. A cross-sectional observational study was conducted, including 306 patients with CHD who had a documented outpatient visit at pediatric cardiology before age 18 years. In all, 210 patients (68.6%) were in cardiac follow-up; 20 (6.5%) withdrew from follow-up and 76 (24.9%) were untraceable. Overall, 198 patients were followed up in tertiary care, 1/4 (n = 52) of which were seen at a formalized ACHD care program and 3/4 (n = 146) remained at pediatric cardiology. Of those followed in formalized ACHD and pediatric cardiology care, the recommended frequency was implemented in 94.2% and 89%, respectively (p = 0.412). No predictors for the implementation of the guidelines were identified. Risk factors for becoming untraceable were none or lower number of heart surgeries, health insurance issues, and nonwhite ethnicity. In conclusion, a significant number of adults continue to be cared for by pediatric cardiologists, indicating that transfer to adult-oriented care was not standard practice. Frequency of follow-up for most patients was in line with the ACC/AHA 2008 guidelines. A considerable proportion of young adults were untraceable in the system, which makes them vulnerable for discontinuation of care.
Keywords: adult; adult disease; aortic coarctation; aortic valve disease; article; cardiac patient; cardiologist; congenital heart disease; cross-sectional study; Ebstein anomaly; endocardial cushion defect; ethnicity; Fallot tetralogy; female; follow up; frequency; great vessels transposition; health care planning; health insurance; health program; heart atrium septum defect; heart catheterization; heart single ventricle; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; major clinical study; male; medical record review; medical society; mitral valve disease; observational study; pediatric cardiology; practice guideline; priority journal; pulmonary valve atresia; pulmonary valve disease; pulmonary vein malformation; risk factor; self report; tertiary health care; tricuspid valve atresia; young adult

The strong association of left-side heart anomalies with Kabuki syndrome - Yoon, J.K.; Ahn, K.J.; Kwon, B.S.; Kim, G.B.; Bae, E.J.; Noh, C.I.; Ko, J.M. (Korean Journal of Pediatrics, 2015)
Purpose: Kabuki syndrome is a multiple congenital malformation syndrome, with characteristic facial features, mental retardation, and skeletal and congenital heart anomalies. However, the cardiac anomalies are not well described in the Korean population. We analyzed the cardiac anomalies and clinical features of Kabuki syndrome in a single tertiary center. Methods: A retrospective analysis was conducted for a total of 13 patients with Kabuki syndrome. Results: The median age at diagnosis of was 5.9 years (range, 9 days to 11 years and 8 months). All patients showed the characteristic facial dysmorphisms and congenital anomalies in multiple organs, and the diagnosis was delayed by 5.9 years (range, 9 days to 11 years and 5 months) after the first visit. Noncardiac anomalies were found in 84% of patients, and congenital heart diseases were found in 9 patients (69%). All 9 patients exhibited left-side heart anomalies, including hypoplastic left heart syndrome in 3, coarctation of the aorta in 4, aortic valve stenosis in 1, and mitral valve stenosis in 1. None had right-side heart disease or isolated septal defects. Genetic testing in 10 patients revealed 9 novel MLL2 mutations. All 11 patients who were available for follow-up exhibited developmental delays during the median 4 years (range, 9 days to 11 years 11 months) of follow-up. The leading cause of death was hypoplastic left heart syndrome. Conclusion: Pediatric cardiologist should recognize Kabuki syndrome and the high prevalence of left heart anomalies with Kabuki syndrome. Genetic testing can be helpful for early diagnosis and counseling.
Keywords: mixed lineage leukemia protein; angiography; aortic coarctation; aortic valve stenosis; article; child; clinical article; computer assisted tomography; congenital heart malformation; disease association; echocardiography; electrocardiography; face dysmorphia; female; follow up; gene mutation; genetic analysis; heart catheterization; human; hypoplastic left heart syndrome; infant; Kabuki makeup syndrome; male; mitral valve stenosis; multiple organ failure; newborn; prevalence; retrospective study; thorax radiography

Risk factors of post-cardiac surgery diaphragmatic paralysis in children with congenital heart disease - Akbariasbagh, P.; Mirzaghayan, M.R.; Akbariasbagh, N.; Shariat, M.; Ebrahim, B. (Journal of Tehran University Heart Center, 2015)
Background: Injured phrenic nerve secondary to cardiac surgeries is the most common cause of diaphragmatic paralysis (DP) in infants. The aim of this study was to determine the risk factors for DP caused by congenital heart defect corrective surgeries in pediatrics. Methods: This cross-sectional study, conducted in a 2-year period (2006–2008), included 451 children with congenital heart diseases admitted to the Pediatric Cardiac Surgery Ward of Imam Khomeini Hospital. The diaphragmatic function was examined via fluoroscopy, and the frequency of DP and its relevant parameters were evaluated. Results: Of the 451 patients, comprising 268 males and 183 females at an age range of 3 days to 204 months (28.2 ± 33.4 months), 25 (5.5%) infants (60% male and 40% female, age range = 15 days to 132 months, 41.2 ± 28.1 months) had DP as follows: 48% unilateral right-sided and 36% unilateral left-sided. Additionally, 68% had cyanotic congenital heart disease and 84% had DP following total correction surgery. The highest prevalence rates of DP resulting in phrenic hemiparesis were observed after arterial switch operation, Fontan procedure, and Blalock–Taussig shunt surgery, respectively. Thirteen (52%) of the 25 DP patients underwent surgical diaphragmatic plication because of severe respiratory distress and dependency on mechanical ventilation, and most of the cases of plication underwent arterial switch operation. The rate of mortality was 24% (6 patients). Conclusion: DP with a prevalence of 5.5% was one of the most common complications secondary to cardiac surgeries in the infants included in the present study. Effective factors were age, weight, cyanotic congenital heart defects, and previous cardiac surgery. Diaphragmatic plication improved prognosis in severe cases.
Keywords: arterial switch operation; article; artificial ventilation; Blalock Taussig shunt; child; child health care; childhood mortality; congenital heart disease; controlled study; cross-sectional study; cyanotic heart disease; descriptive research; diaphragm movement; diaphragm paralysis; female; fluoroscopy; Fontan procedure; heart surgery; human; infant; Iran; major clinical study; male; phrenic nerve paralysis; prevalence; respiratory distress; risk assessment; risk factor; surgical diaphragmatic plication; thorax surgery

Association of Interstage Home Monitoring with Mortality, Readmissions, and Weight Gain: A Multicenter Study from the National Pediatric Cardiology Quality Improvement Collaborative - Oster, M.E.; Ehrlich, A.; King, E.; Petit, C.J.; Clabby, M.; Smith, S.; Glanville, M.; Anderson, J.; Darbie, L.; Beekman, R.H. (Circulation, 2015)
Background-Daily home monitoring of oxygen saturation and weight has been reported to improve outcomes for patients with single-ventricle heart disease during the period between stage I palliation and stage II palliation. However, these studies have been limited to single institutions and used historical control subjects. Our objective was to determine the association of various interstage home monitoring strategies with outcomes using a multicenter cohort with contemporary control subjects. Methods and Results-We performed a retrospective cohort study using prospectively collected data from the National Pediatric Cardiology Quality Improvement Collaborative from 2008 to 2012. We compared interstage mortality, unscheduled readmissions, and change in weight-for-age Z score for various home monitoring strategies of oxygen saturation (n=494) or weight (n=472), adjusting for sex, syndrome, tricuspid regurgitation, arch obstruction, and shunt type. Overall interstage mortality was 8.1%, and 47% had ≥1 unscheduled readmission. We did not find any associations of home oxygen saturation or weight monitoring with mortality or readmission. Although there was no difference in weight-for-age Z score for daily (0.33±0.12) versus weekly (0.34±0.18, P=0.98) weight monitoring, daily home weight monitoring was superior to no home weight monitoring (-0.15±0.18; P<0.01). Conclusions-Home weight monitoring is associated with improved weight gain during the interstage period, but we did not find any benefits in other clinical outcomes for either home oxygen saturation monitoring or home weight monitoring.
Keywords: aortic arch anomaly; article; Blalock Taussig shunt; cardiovascular mortality; cohort analysis; controlled study; echocardiography; female; heart ventricle function; home monitoring; hospital readmission; human; interstage home monitoring; major clinical study; male; multicenter study; outcome assessment; oxygen saturation; priority journal; prospective study; quality of life; retrospective study; sex; tricuspid valve regurgitation; body weight gain

Combined surgical and interventional approaches for treating patients with congenital heart disease - Vida, V.L.; Guariento, A.; Zucchetta, F.; Padalino, M.A.; Milanesi, O.; Maschietto, N.; Stellin, G. (Journal of Cardiac Surgery, 2015)
Aims During the last decade the cooperation between surgeons and cardiologists has further expanded by combining surgical and interventional techniques (CCBSI) performed in the operating room, without the use of fluoroscopy. We sought to evaluate the results of our experience with CCBSI. Methods All children with congenital heart disease (CHD) who underwent a CCBSI in the operating room between June 2007 and January 2014 were enrolled. Results Sixty-eight patients were included. Median age at CCBSI was five months (range 1-48 months). The three main diagnoses leading to surgery included: (1) tetralogy of Fallot (TOF) (n = 40), (2) muscular ventricular septal defects (VSD) (n = 12), (3) single ventricle with pulmonary artery branch stenosis (n = 4). There were 72 catheter-based procedures associated with surgical maneuvres, including: (1) transatrial balloon dilation (BD) of the pulmonary valve (n = 45), (2) transinfundibular BD of the main pulmonary artery trunk (n = 12), (3) perventricular VSD closure with septal occluder (n = 8), (4) BD of pulmonary artery branches (n = 5), and other less common procedures (n = 2). There were no procedure-related complications and no hospital deaths. Median follow-up time was four years (range 0.95-7.9 years). There was one late death for respiratory distress after transapical balloon dilation of the aortic valve. One patient required BD and stenting of the left pulmonary artery branch 3.6 years after intraoperative BD for residual stenosis. Conclusions The CCBSI represents a safe and effective treatment for selected patients with complex CHD. It will be helpful in minimizing patients' surgical trauma and in shortening or avoiding the use of cardiopulmonary bypass.
Keywords: article; balloon dilatation; child; combining surgical and interventional technique; congenital heart disease; Fallot tetralogy; follow up; heart single ventricle; heart surgery; heart ventricle septum defect; human; infant; interventional cardiovascular procedure; major clinical study; operating room; preschool child; pulmonary artery; pulmonary artery stenosis; pulmonary valve; respiratory distress; septal occluder; transatrial balloon dilation; transinfundibular balloon dilation

Adult congenital heart disease - Weale, J.; Kelleher, A.A. (Anaesthesia and Intensive Care Medicine, 2015)
Continued advances in the understanding and management of congenital heart disease (CHD) mean that over 90% of children born with CHD now survive to adulthood. This in turn results in greater numbers of adult patients presenting for medical and surgical care at non-specialist centres. A simple classification of adult congenital heart disease (ACHD) according to complexity can help clinicians to understand the implications of the specific cardiac anomaly encountered. Issues relating to the conduct of anaesthesia in ACHD patient include careful attention to euvolaemia, the preservation of sinus rhythm and cardiac output, and in complex patients manipulating the balance between systemic and pulmonary blood flows. Additionally, effective antibiotic prophylaxis and the prevention of either excessive bleeding or thromboembolism are vitally important. It should not be forgotten that although many patients with simple or repaired cardiac lesions may be very well managed in a non-specialist unit, those with Eisenmenger's syndrome or severe pulmonary hypertension have an extremely high risk of death in the perioperative period, and in all but life-threatening situations should always be managed within specialist centres.
Keywords: anesthetic agent; adult congenital heart disease; anesthesia; anesthesia level; antibiotic prophylaxis; article; atrioventricular septal defect; bleeding; congenital heart disease; disease classification; Ebstein anomaly; Eisenmenger complex; Fallot tetralogy; heart arrhythmia; heart atrium septum defect; heart failure; heart injury; heart ventricle septum defect; human; hypoplastic left heart syndrome; postoperative care; pregnancy; priority journal; psychological aspect; pulmonary hypertension; pulmonary valve atresia; regional anesthesia; thromboembolism

Parental Vigilance in Caring for Their Children with Hypoplastic Left Heart Syndrome - Meakins, L.; Ray, L.; Hegadoren, K.; Rogers, L.G.; Rempel, G.R. (Pediatric nursing, 2015)
Hypoplastic left heart syndrome (HLHS) is a complex heart malformation that requires life-saving treatments. Parents experience numerous challenges as they learn to parent a child with complex care requirements. The following research question guided this qualitative study: Is the parenting process among parents of a child with HLHS characterized by exaggerated vigilant parental action, and if so, how does this influence parental response? Situated within a larger program of pediatric cardiology research, this study included data from two grounded theory studies with parents of children with HLHS. This secondary analysis involved a thematic content analysis using sensitizing concepts of uncertainty, protectiveness, support, and mastery of complex care. Transcribed data from 55 interviews with 24 mothers and 17 fathers of young children with HLHS were analyzed for relevant and recurring themes. In mastering skills required to care for their child with HLHS, parents contrasted what was in their hands with what was out of their hands. Vigilant parental actions were evident as parents became skilled at providing complex care. Parents said they were sometimes excessive in their vigilant actions. In retrospect they viewed this vigilance as appropriate in some situations but exaggerated in other situations. Understanding parents' vigilant actions in response to their child's complex care can guide health care providers' interactions with families. Long-term follow up, both clinically and through research, is needed to assess the long-term consequences of exaggerated vigilant parental action on the child, parent, and family, and to determine and evaluate appropriate and timely intervention.
Keywords: adaptive behavior; adult; attention; caregiver; female; human; hypoplastic left heart syndrome; interview; male; middle aged; nursing; parent; psychology; qualitative research; social support; uncertainty

Chronic neuromotor disability after complex cardiac surgery in early life - Ricci, M.F.; Andersen, J.C.; Joffe, A.R.; Watt, M.-J.; Moez, E.K.; Dinu, I.A.; Guerra, G.G.; Ross, D.B.; Rebeyka, I.M.; Robertson, C.M.T. (Pediatrics, 2015)
BACKGROUND AND OBJECTIVES: Little is known about chronic neuromotor disability (CND) including cerebral palsy and motor impairments after acquired brain injury in children surviving early complex cardiac surgery (CCS). We sought to determine the frequency and presentation of CND in this population while exploring potentially modifiable acute care predictors. METHODS: This prospective follow-up study included 549 children after CCS requiring cardiopulmonary bypass at ≤6 weeks of age. Groups included those with only 1 CCS, mostly biventricular CHD, and those with .1 CCS, predominantly single ventricle defects. At 4.5 years of age, 420 (94.6%) children received multidisciplinary assessment. Frequency of CND is given as percentage of assessed survivors. Predictors of CND were analyzed using multiple logistic regression analysis. RESULTS: CND occurred in 6% (95% confidence interval [CI] 3.7%-8.2%) of 4.5-year survivors; for 1 CCS, 4.2% (CI 2.3%-6.1%) and >1, 9.8% (CI 7%-12.6%). CND presentation showed: hemiparesis, 72%; spasticity, 80%; ambulation, 72%; intellectual disability, 44%; autism, 16%; epilepsy, 12%; permanent vision and hearing impairment, 12% and 8%, respectively. Overall, 32% of presumed causative events happened before first CCS. Independent odds ratio for CND are age (days) at first CCS, 1.08 (CI 1.04-1.12; P < .001); highest plasma lactate before first CCS (mmol/L), 1.13 (CI 1.03-1.23; P = 0.008); and >1 CCS, 3.57 (CI 1.48-8.9; P = .005). CONCLUSIONS: CND is not uncommon among CCS survivors. The frequency of associated disabilities characterized in this study informs pediatricians caring for this vulnerable population. Shortening the waiting period and reducing preoperative plasma lactate levels at first CCS may assist in reducing the frequency of CND.
Keywords: lactic acid; acquired brain injury; article; autism; cardiopulmonary bypass; child; chronic neuromotor disability; cohort analysis; complex cardiac surgery; congenital heart disease; epilepsy; female; follow up; hearing impairment; heart surgery; hemiparesis; human; intellectual impairment; lactate blood level; major clinical study; male; motor dysfunction; postoperative period; preschool child; priority journal; prospective study; spasticity; survival rate; visual impairment; walking difficulty

Tricuspid atresia 18 years post Glenn: Is Fontan necessary in all cases? - Williams-Phillips, S. (West Indian Medical Journal, 2015)
Tricuspid atresia is a rare cyanotic congenital heart disease, first described by Kreysig (1817), with an incidence of 1%to 5%. It is incompatible with longevity without surgical intervention. Glenn (1958) was successful in using a superior vena cava to right pulmonary artery anastomosis. Fontan (1958) was successful in separating the right and left cardiac circulation; this is the surgical method of choice, with death of 17% by 20 years of age. The Fontan circulation has burdens of multisystem abnormalities, including ventricular dysfunction (72%), dysrhythmias (40%) and renal, hepatic, gastrointestinal and pulmonary complications. The index case is the oldest documented report of tricuspid atresia with rudimentary right ventricle and concordant ventriculo-arterial connections, 18 years post Glen only, from two years of age. She is asymptomatic, of high intellect, never used medications and is now functioning at New York Heart Association (NYHA) I-II at 20 years of age. Her survival and function was secondary to an innate large atrial and ventricular communication with normal left ventricle, mitral, aortic and pulmonary valves, indicating Fontan may not be needed in all structural anatomic cases of tricuspid atresia.
Keywords: hemoglobin; adult; article; body dysmorphic disorder; case report; cyanosis; digital clubbing; electrocardiography; female; Fontan procedure; Glenn shunt; hemoglobin blood level; human; longevity; medical decision making; New York Heart Association class; pulmonary artery; rare disease; superior cava vein; transthoracic echocardiography; tricuspid valve atresia; urinalysis; young adult

Megalencephaly, polymicrogyria, polydactyly and hydrocephalus (MPPH) syndrome: A new case with occipital encephalocele and cleft palate - Demir, N.; Peker, E.; Gülşen, I.; Kaba, S.; Tuncer, O. (Genetic Counseling, 2015)
Megalencephaly, polymicrogyria, polydactyly and hydrocephalus (MPPH) syndrome: a new case with occipital encephalocele and cleft palate: The megalencephaly, polymicrogyria, polydactyly, and hydrocephalus (MPPH) syndrome is quite rarely seen. The four main findings in this syndrome may be accompanied by severe psychomotor retardation, blindness, hypotonia, convulsions, and facial dysmorphism. In this paper, we present a female newborn at 39 weeks gestational age bom to parents who are first degree cousins. Beside the facial dysmorphism and four main features of the MPPH syndrome, the findings on the physical examination of the patient were, hypertonicity, occipital encephalocele, cleft palate, and multiple polyps in the tongue. The presence of occipital encephalocele, cleft palate, and polyps in the tongue in this patient was not reported previously in the literature.
Keywords: phenobarbital; anticonvulsant therapy; article; blindness; brain ventricle dilatation; brain ventricle peritoneum shunt; case report; chromosome; cleft palate; clinical feature; computer assisted tomography; congenital disorder; convulsion; disseminated intravascular clotting; electroencephalography; encephalocele; epilepsy; face dysmorphia; female; fetus echography; first-degree relative; gestational age; heart single ventricle; human; intubation; karyotype 46,XY; lateral brain ventricle; MPPH syndrome; muscle hypotonia; neonatal respiratory distress syndrome; newborn; newborn intensive care; nuclear magnetic resonance imaging; occipital encephalocele; parent; perinatal period; physical examination; psychomotor retardation; sepsis; shunt infection; tongue disease; tongue polyp

Anomalous Origin of Coronary Artery From Main Pulmonary Artery in Hypoplastic Left Heart Syndrome - Turiy, Y.; Douglas, W.; Balaguru, D. (Annals of Thoracic Surgery, 2015)
We report a case of anomalous origin of the left anterior descending coronary artery (LAD) from the main pulmonary artery in a child with hypoplastic left heart syndrome (mitral atresia/aortic atresia). Mechanical circulatory support was necessary because of the inability to wean from cardiopulmonary bypass after the Norwood procedure. The patient died at 4 months of age having continued depressed right ventricular function. The diagnosis was made during a catheterization performed 6 weeks after surgery because of concern for stenosis of Blalock-Taussig shunt. We believe his prolonged postoperative recovery and eventual demise can partially be attributed to lack of cardioplegia to the anomalous LAD territory during surgery.
Keywords: Blalock Taussig shunt; prostaglandin; anastomosis; aortic valve disease; aortic valve atresia; artery surgery; article; assisted circulation; balloon dilatation; balloon valvuloplasty catheter; Blalock Taussig shunt; Blalock Taussig shunt stenosis; brachiocephalic trunk; cardioplegia; cardiopulmonary bypass; case report; cause of death; coronary artery anomaly; coronary artery circumflex branch; coronary stent; Damus Kaye Stansel anastomosis; echocardiography; extracorporeal oxygenation; heart catheterization; heart failure; heart murmur; heart right ventricle function; human; hypoplastic left heart syndrome; infant; intensive care unit; left anterior descending coronary artery; low birth weight; metabolic acidosis; mitral valve atresia; mixed infection; Norwood procedure; oxygen desaturation; polytetrafluoroethylene implant; postoperative period; priority journal; pulmonary artery; right coronary artery; sepsis; shunt occlusion; ST segment elevation; weaning; Tyshak Mini balloon; Veriflex MR stent

Prevalence of birth defects in an Arctic Russian setting from 1973 to 2011: A register-based study - Postoev, V.A.; Nieboer, E.; Grjibovski, A.M.; Odland, J.Ø. (Reproductive Health, 2015)
Background: Birth defects (BD) constitute an important public health issue as they are the main cause of infant death. Their prevalence in Europe for 2008-2012 was 25.6 per 1000 newborns. To date, there are no population-based studies for the Russian Federation. The aim of the present study is to estimate the prevalence of BD, its forms, and changes over time in the Russian Arctic city of Monchegorsk (Murmansk County) for the period 1973-2011. Methods: The Murmansk County Birth Register and the Kola Birth Register were the primary sources of information, covering 30448 pregnancy outcomes in Monchegorsk (Murmansk County, Russia) during the study period. Results: The total perinatal prevalence of BD was 36.1/1000 live births (LB) and stillborn (SB) (95% CI = 34.0-38.2). After exclusions of minor malformations according to the European Surveillance of Congenital Anomalies guidelines, it decreased to 26.5/1000 LB plus SB (95% CI = 24.6-28.3). The perinatal prevalence of BD that are obligatory to report in Russia was 7.3/1000 LB plus SB (95% CI = 6.4-8.3). There was a significant positive time-trend in total perinatal prevalence of birth defects across the study period (p < 0.001 for trend). Prevalence of all BD increased from 23.5/1000 to 46.3/1000 (LB plus SB), while that excluding minor defects rose from 17.7/1000 to 35.7/1000 (LB plus SB). The most prevalent group of defects was malformations of the musculoskeletal system, which represented 35.4% of all BD. The most prominent increase was observed for the urinary system, rising from 0.2/1000 to 19.1/1000 (LB plus SB). Conclusions: The observed perinatal prevalence of BD in Monchegorsk increased two-fold during the 38-year study period. Further investigations to identify the underlying bases for the observed progressive growth in BD are recommended.
Keywords: anencephalus; anophthalmia; anus atresia; Arctic; article; bladder exstrophy; cleft lip; cleft palate; congenital hydrocephalus; congenital malformation; controlled study; diaphragm hernia; Down syndrome; encephalocele; epispadias; esophagus atresia; gastroschisis; great vessels transposition; human; hypoplastic left heart syndrome; hypospadias; kidney agenesis; limb malformation; live birth; major clinical study; microtia; newborn; omphalocele; pregnancy outcome; prevalence; Russian Federation; spinal dysraphism; stillbirth; trend study

Executive Function in Children and Adolescents with Critical Cyanotic Congenital Heart Disease - Cassidy, A.R.; White, M.T.; DeMaso, D.R.; Newburger, J.W.; Bellinger, D.C. (Journal of the International Neuropsychological Society : JINS, 2015)
Children and adolescents with critical cyanotic congenital heart disease (CHD) are at risk for deficits in aspects of executive function (EF). The primary aim of this investigation was to compare EF outcomes in three groups of children/adolescents with severe CHD and controls (ages 10-19 years). Participants included 463 children/adolescents with CHD [dextro-transposition of the great arteries (TGA), n=139; tetralogy of Fallot (TOF), n=68; and, single-ventricle anatomy requiring Fontan procedure (SVF), n=145] and 111 controls, who underwent laboratory and informant-based evaluation of EF skills. Rates of EF impairment on D-KEFS measures were nearly twice as high for CHD groups (75-81%) than controls (43%). Distinct EF profiles were documented between CHD groups on D-KEFS tasks. Deficits in flexibility/problem-solving and verbally mediated EF skills were documented in all three CHD groups; visuo-spatially mediated EF abilities were impaired in TOF and SVF groups, but preserved in TGA. Parent, teacher, and self-report ratings on the BRIEF highlighted unique patterns of metacognitive and self-regulatory concerns across informants. CHD poses a serious threat to EF development. Greater severity of CHD is associated with worse EF outcomes. With increased understanding of the cognitive and self-regulatory vulnerabilities experienced by children and adolescents with CHD, it may be possible to identify risks early and provide individualized supports to promote optimal neurodevelopment.
Keywords: adolescent; analysis of variance; child; cognitive defect; complication; congenital heart malformation; depth perception; executive function; female; human; male; neuropsychological test; photostimulation; physiology; questionnaire; young adult

Important knowledge for parents of children with heart disease: Parent, nurse, and physician views - Daily, J.; Fitzgerald, M.; Downing, K.; King, E.; Del Rey, J.G.; Ittenbach, R.; Marino, B. (Cardiology in the Young, 2014)
Objectives Parental understanding of their children's heart disease is inadequate, which may contribute to poor health outcomes. The purpose of this study was to determine what parental knowledge is important in the care of children with heart disease from the perspective of parents, nurses, and physicians. Methods Focus groups were formed with parents of children with single ventricle congenital heart disease (CHD), biventricular CHD, and heart transplantation, and with nurses and physicians who provide care for these children. A nominal group technique was used to identify and prioritise important parental knowledge items and themes. The voting data for each theme were reported by participant type - parent, nurse, and physician - and patient diagnosis - single ventricle CHD, biventricular CHD, and heart transplantation. Results The following three themes were identified as important by all groups: recognition of and response to clinical deterioration, medications, and prognosis and plan. Additional themes that were unique to specific groups included the following: medical team members and interactions (parents), tests and labs (parents), neurodevelopmental outcomes and interventions (physicians), lifelong disease requiring lifelong follow-up (physicians and nurses), and diagnosis, physiology, and interventions (single ventricle and biventricular CHD). Conclusions Parents, nurses, and physicians have both common and unique views regarding what parents should know to effectively care for their children with single ventricle CHD, biventricular CHD, or heart transplantation. Specific targeted parental education that incorporates these findings should be provided to each group. Further development of questionnaires regarding parental knowledge with appropriate content validity is warranted.
Keywords: adult; article; child; child health care; clinical article; clinical assessment; congenital heart disease; demography; ethnicity; exercise; female; follow up; health care planning; heart transplantation; human; knowledge; male; nurse attitude; outcome assessment; parental attitude; physician attitude; prognosis; resource allocation

Minimizing the risk of preoperative brain injury in neonates with aortic arch obstruction - Algra, S.O.; Haas, F.; Poskitt, K.J.; Groenendaal, F.; Schouten, A.N.J.; Jansen, N.J.G.; Azakie, A.; Gandhi, S.; Campbell, A.; Miller, S.P.; McQuillen, P.S.; De Vries, L.S. (Journal of Pediatrics, 2014)
Objective To determine whether prenatal diagnosis lowers the risk of preoperative brain injury by assessing differences in the incidence of preoperative brain injury across centers. Study design From 2 prospective cohorts of newborns with complex congenital heart disease studied by preoperative cerebral magnetic resonance imaging, one cohort from the University Medical Center Utrecht (UMCU) and a combined cohort from the University of California San Francisco (UCSF) and University of British Columbia (UBC), patients with aortic arch obstruction were selected and their imaging and clinical course reviewed. Results Birth characteristics were comparable between UMCU (n = 33) and UCSF/UBC (n = 54). Patients had a hypoplastic aortic arch with either coarctation/interruption or hypoplastic left heart syndrome. In subjects with prenatal diagnosis, there was a significant difference in the prevalence of white matter injury (WMI) between centers (11 of 22 [50%] at UMCU vs 4 of 30 [13%] at UCSF/UBC; P <.01). Prenatal diagnosis was protective for WMI at UCSF/UBC (13% prenatal diagnoses vs 50% postnatal diagnoses; P <.01), but not at UMCU (50% vs 46%, respectively; P >.99). Differences in clinical practice between prenatally diagnosed subjects at UMCU vs UCSF/UBC included older age at surgery, less time spent in the intensive care unit, greater use of diuretics, less use of total parenteral nutrition (P <.01), and a greater incidence of infections (P =.01). In patients diagnosed postnatally, the prevalence of WMI was similar in the 2 centers (46% at UMCU vs 50% at UCSF/UBC; P >.99). Stroke prevalence was similar in the 2 centers regardless of prenatal diagnosis (prenatal diagnosis: 4.5% at Utrecht vs 6.7% at UCSF/UBC, P =.75; postnatal diagnosis: 9.1% vs 13%, respectively, P >.99). Conclusion Prenatal diagnosis can be protective for WMI, but this protection may be dependent on specific clinical management practices that differ across centers.
Keywords: antibiotic agent; diuretic agent; inotropic agent; prostaglandin E2; aortic arch anomaly; aortic arch interruption; aortic coarctation; aortic arch obstruction; Apgar score; article; artificial ventilation; bloodstream infection; brain injury; cerebrovascular accident; cesarean section; clinical practice; clinical study; coagulase negative Staphylococcus; congenital heart disease; diffusion weighted imaging; disease course; echo planar imaging; female; human; hypoplastic left heart syndrome; incidence; infant; intensive care unit; major clinical study; male; nuclear magnetic resonance imaging; pneumonia; prenatal diagnosis; preoperative complication; prevalence; prospective study; risk factor; risk reduction; Staphylococcus infection; total parenteral nutrition; white matter injury

Major congenital anomalies in babies born with Down syndrome: A EUROCAT population-based registry study - Morris, J.K.; Garne, E.; Wellesley, D.; Addor, M..-C.; Arriola, L.; Barisic, I.; Beres, J.; Bianchi, F.; Budd, J.; Dias, C.M.; Gatt, M.; Klungsoyr, K.; et al. (American Journal of Medical Genetics, Part A, 2014)
Previous studies have shown that over 40% of babies with Down syndrome have a major cardiac anomaly and are more likely to have other major congenital anomalies. Since 2000, many countries in Europe have introduced national antenatal screening programs for Down syndrome. This study aimed to determine if the introduction of these screening programs and the subsequent termination of prenatally detected pregnancies were associated with any decline in the prevalence of additional anomalies in babies born with Down syndrome. The study sample consisted of 7,044 live births and fetal deaths with Down syndrome registered in 28 European population-based congenital anomaly registries covering seven million births during 2000-2010. Overall, 43.6% (95% CI: 42.4-44.7%) of births with Down syndrome had a cardiac anomaly and 15.0% (14.2-15.8%) had a non-cardiac anomaly. Female babies with Down syndrome were significantly more likely to have a cardiac anomaly compared to male babies (47.6% compared with 40.4%, P<0.001) and significantly less likely to have a non-cardiac anomaly (12.9% compared with 16.7%, P<0.001). The prevalence of cardiac and non-cardiac congenital anomalies in babies with Down syndrome has remained constant, suggesting that population screening for Down syndrome and subsequent terminations has not influenced the prevalence of specific congenital anomalies in these babies.
Keywords: abdominal wall defect; annular pancreas; anophthalmia; anus atresia; aortic coarctation; aortic valve stenosis; aortic valve atresia; article; atrioventricular septal defect; bladder exstrophy; choana atresia; cleft lip; cleft lip palate; cleft palate; congenital cataract; congenital glaucoma; congenital heart malformation; congenital malformation; congenital skin disease; controlled study; craniofacial synostosis; diaphragm hernia; digestive system malformation; Down syndrome; duodenum atresia; duodenum stenosis; ear malformation; Ebstein anomaly; epispadias; esophagus atresia; European; eye malformation; face malformation; Fallot tetralogy; female; fetus death; gender; genital malformation; great vessels transposition; heart atrium septum defect; heart single ventricle; heart ventricle septum defect; Hirschsprung disease; human; hydrocephalus; hydronephrosis; hypoplastic right heart; hypospadias; intestine atresia; intestine stenosis; kidney agenesis; kidney dysplasia; limb malformation; limb reduction defect; live birth; major clinical study; male; microcephaly; mouth malformation; neck malformation; nervous system malformation; neural tube defect; newborn; omphalocele; patent ductus arteriosus; perinatal mortality; polydactyly; population research; Potter syndrome; prenatal screening; prevalence; priority journal; prune belly syndrome; pulmonary valve atresia; pulmonary valve stenosis; rectal stenosis; register; respiratory tract malformation; syndactyly; talipes equinovarus; terminations of pregnancy for fetal anomaly; tracheoesophageal fistula; trend study; tricuspid valve atresia; tricuspid valve stenosis; urinary tract malformation

Genetic knowledge and attitudes of parents of children with congenital heart defects - Fitzgerald-Butt, S.M.; Klima, J.; Kelleher, K.; Chisolm, D.; Mcbride, K.L. (American Journal of Medical Genetics, Part A, 2014)
Clinical genetic testing for specific isolated congenital heart defects (CHD) is becoming standard of care in pediatric cardiology practice. Both genetic knowledge and attitudes toward genetic testing are associated with an increased utilization of genetic testing, but these factors have not been evaluated in parents of children with CHD. We mailed a survey to measure the demographics, genetic knowledge, and attitudes towards genetic testing of parents of children with CHD who previously consented to participate in a separate research study of the genetic etiology of left ventricular outflow tract malformations (LVOT). Of the 378 eligible families, 190 (50%) returned surveys with both parents completing surveys in 97 (51%) families, resulting in 287 participants. Genetic knowledge was assessed on an adapted measure on which the mean percent correct was 73.8%. Educational attainment and household income were directly and significantly associated with genetic knowledge (P<0.001). Attitudes about the health effects of genetic testing were favorable with at least 57% agreeing that genetic testing would be used for managing health care and finding cures for disease. Conversely, a minority of participants found it likely that genetic testing would be used for insurance (up to 39.9%), employment (15.8%), or racial/social discrimination (up to 11.2%). Parents of younger children were less likely to endorse employment or racial/social discrimination. Genetic knowledge was not correlated with specific attitudes. Among parents of children with CHD, genetic knowledge was directly associated with household income and education, but additional research is necessary to determine what factors influence attitudes towards genetic testing.
Keywords: adolescent; adult; aortic coarctation; article; attitude to health; bicuspid aortic valve; child; child health care; congenital heart malformation; educational status; employment; female; genetic knowledge; genetic screening; genetics; health care survey; health insurance; heart left ventricle outflow tract obstruction; human; hypoplastic left heart syndrome; income; infant; knowledge; major clinical study; male; parental attitude; preschool child; priority journal; racism; school child; social discrimination; social status; young adult

Sonographic dynamic assessment of lung injury in a child with hypoplastic left heart syndrome undergoing extracorporeal membrane oxygenation - Biasucci, D.G.; Ricci, Z.; Conti, G.; Cogo, P. (Pediatric Pulmonology, 2014)
Introduction: Performed for many years in clinical settings, pleural and lung ultrasound (PLUS) has emerged to be an invaluable tool to diagnose underlying conditions of respiratory failure, to monitor disease progression and to ensure appropriate therapeutic intervention. PLUS basically relies on the analysis of two prevalent ultrasound artefacts: A-lines and B-lines. A-lines are hyperechoic reverberation artefacts of the pleural line. A-lines combined with lung sliding show that lungs are well aerated. B-lines are vertical hyperechoic reverberation artefacts arising from pleural line extending to the bottom of the screen. The prevalence of B-lines indicates a pathologic parenchyma. Since PLUS is readily available, easily affordable, and biologically non-invasive, it is especially suitable for bedside clinical care in critically ill and unstable adult patients. Several authors have recently proposed PLUS for application in critically ill neonates and children. We report a case in which PLUS was used to clinically monitor a complex lung lesion during treatment of a child with congenital heart disease suffering from severe lung injury. Case Description: A 1-year-old male with hypoplastic left heart syndrome underwent bidirectional Glenn procedure and systemic-to-left pulmonary artery shunt for heart palliation. After surgery, he developed a severe acute respiratory distress syndrome (ARDS) and extra-corporeal membrane oxygenation (ECMO) treatment was started. PLUS was performed daily to monitor the disease's progression and response to treatment during lung rest. As B-lines were decreasing and A-lines were becoming visible, we were able to monitor the improving aeration of the injured lung. The ultrasound showed high consistency with traditional imaging. Discussion: Due to its non-ionizing nature, low cost, easy availability, easy repeatability and real-time results, PLUS is a feasible and beneficial bedside imaging technique for critically ill and unstable adult and pediatric patients. A reliable monitoring of ongoing treatments is certainly helpful to provide appropriate intervention, correctly schedule chest X-ray and CT-scan, and optimize ECMO weaning. The present case suggests that PLUS may be a successful and useful tool for monitoring lung diseases in children with CHD with severe postoperative complex lung injury.
Keywords: adult respiratory distress syndrome; aortopulmonary shunt; article; artificial ventilation; case report; child; disease course; echography; extracorporeal oxygenation; Glenn shunt; human; hypoplastic left heart syndrome; lung compliance; lung gas exchange; lung infarction; male; preschool child; treatment response

Cor triloculare biatriatum--A case report - Agnihotri, G.; Mahajan, D. (Nepal Medical College journal : NMCJ, 2014)
Cor triloculare biatriatum or double inlet single ventricle is a congenital heart defect in which both atria are connected to a common or dominant ventricle. The present report presents an index case and describes the embryological basis and clinical aspects of this extremely rare anomaly. A three months old infant presented with extreme respiratory distress without cyanosis and repeated chest infections. The patient was diagnosed to be a case of single ventricle with both atria opening in the common ventricular chamber. The common ventricular chamber (single ventricle) was connected to a rudimentary outflow tract. The great arteries were in a position of d-transposition of great arteries. However, there was no pulmonary or aortic stenosis. A clear concept and awareness regarding this condition and its clinical manifestations is bound to facilitate timely intervention with improved success rates.
Keywords: case report; congenital heart malformation; congenital malformation; echography; heart ventricle; human; infant; male; neonatal respiratory distress syndrome; respiratory tract infection

Aldosterone-cortisol imbalance immediately after Fontan operation with implications for abnormal fluid homeostasis - Saiki, H.; Kuwata, S.; Kurishima, C.; Iwamoto, Y.; Ishido, H.; Masutani, S.; Senzaki, H. (American Journal of Cardiology, 2014)
Abnormal water metabolism is frequently observed after Fontan surgery. We hypothesized that patients' adrenal hormones show unique responses immediately after Fontan operation and that such a hormonal profile is related to postoperative hemodynamics and water imbalance. Twenty-eight patients who underwent a Fontan operation (n = 16) or a non-Fontan type operation (n = 12; controls) under cardiopulmonary bypass were studied. Postoperative urine cortisol and aldosterone levels were measured daily to minimize the influence of circadian rhythms and temporal hemodynamic variations. Cortisol excretion was markedly elevated on postoperative day (POD) 0 in controls, consistent with a stress-induced cortisol response. Cortisol excretion was not high on POD 0 in Fontan patients and was markedly lower than that in the controls (444 ± 150 vs 34 ± 6 μg/m2/day, p <0.05), indicating an adrenal insufficiency status. Conversely, aldosterone levels were significantly higher in Fontan patients than in controls immediately after surgery and remained so thereafter. The cortisol-to-aldosterone ratio was significantly lower in Fontan patients on POD 0 (p <0.05 vs controls); low cortisol-to-aldosterone ratios were associated with a longer pleural drainage duration and intensive care unit stay. Daily cortisol and aldosterone levels were significantly associated with postoperative hemodynamics; low cortisol levels correlated with low cardiac and urine outputs, whereas high aldosterone levels correlated with low cardiac output and increased blood pressure and central venous pressure. Thus, aldosterone-to-cortisol imbalance occurred specifically after the Fontan operation. This unique hormonal profile significantly affected patients' postoperative water balance and hemodynamics. Modulation of the adrenal hormone could be useful for reducing postoperative complications after the Fontan operation.
Keywords: aldosterone; creatinine; hydrocortisone; adrenal insufficiency; aldosterone cortisol imbalance; aldosterone urine level; article; ascites; cardiopulmonary bypass; central venous pressure; child; circadian rhythm; clinical article; controlled study; correlation analysis; creatinine clearance; elevated blood pressure; fluid balance; Fontan procedure; forward heart failure; heart hemodynamics; cardiac index; heart output; human; hydrocortisone urine level; intensive care unit; length of stay; mean arterial pressure; metabolic disorder; pleura effusion; postoperative complication; postoperative period; systemic vascular resistance; urine volume; water retention

Maternal depression, antidepressant prescriptions, and congenital anomaly risk in offspring: A population-based cohort study - Ban, L.; Gibson, J.E.; West, J.; Fiaschi, L.; Sokal, R.; Smeeth, L.; Doyle, P.; Hubbard, R.B.; Tata, L.J. (BJOG: An International Journal of Obstetrics and Gynaecology, 2014)
Objective: To estimate risks of major congenital anomaly (MCA) among children of mothers prescribed antidepressants during early pregnancy or diagnosed with depression but without antidepressant prescriptions. Design: Population-based cohort study. Setting: Linked UK maternal-child primary care records. Population: A total of 349 127 singletons liveborn between 1990 and 2009. Methods: Odds ratios adjusted for maternal sociodemographics and comorbidities (aORs) were calculated for MCAs, comparing women with first-trimester selective serotonin reuptake inhibitors (SSRIs) or tricyclic antidepressants (TCAs) and women with diagnosed but unmedicated depression, or women without diagnosed depression. Main: outcome measures Fourteen system-specific MCA groups classified according to the European Surveillance of Congenital Anomalies and five specific heart anomaly groups. Results: Absolute risks of MCA were 2.7% (95% confidence interval, 95% CI, 2.6-2.8%) in children of mothers without diagnosed depression, 2.8% (95% CI 2.5-3.2%) in children of mothers with unmedicated depression, and 2.7% (95% CI 2.2-3.2%) and 3.1% (95% CI 2.2-4.1%) in children of mothers with SSRIs or TCAs, respectively. Compared with women without depression, MCA overall was not associated with unmedicated depression (aOR 1.07, 95% CI 0.96-1.18), SSRIs (aOR 1.01, 95% CI 0.88-1.17), or TCAs (aOR 1.09, 95% CI 0.87-1.38). Paroxetine was associated with increased heart anomalies (absolute risk 1.4% in the exposed group compared with 0.8% in women without depression; aOR 1.78, 95% CI 1.09-2.88), which decreased marginally when compared with women with diagnosed but unmedicated depression (aOR 1.67, 95% CI 1.00-2.80). Conclusions: Overall MCA risk did not increase with maternal depression or with antidepressant prescriptions. Paroxetine was associated with increases of heart anomalies, although this could represent a chance finding from a large number of comparisons undertaken.
Keywords: citalopram; escitalopram; fluoxetine; fluvoxamine; paroxetine; serotonin uptake inhibitor; sertraline; tricyclic antidepressant agent; adolescent; adult; aortic coarctation; arterial trunk; article; atrioventricular septal defect; cardiovascular malformation; chromosome aberration; cohort analysis; comorbidity; conception; congenital heart malformation; congenital malformation; controlled study; digestive system malformation; drug safety; ear malformation; Ebstein anomaly; environmental exposure; eye malformation; face malformation; Fallot tetralogy; female; first trimester pregnancy; genital malformation; head and neck malformation; heart atrium septum defect; heart single ventricle; heart ventricle septum defect; human; limb malformation; lung vein drainage anomaly; major clinical study; major congenital anomaly; musculoskeletal system malformation; neck malformation; nervous system malformation; patent ductus arteriosus; prescription; progeny; postnatal depression; respiratory tract malformation; risk assessment; tricuspid valve atresia; tricuspid valve stenosis; urinary tract malformation

Association of certain chronic maternal diseases with the risk of specific congenital heart defects: A population-based study - Vereczkey, A.; Gerencsér, B.; Czeizel, A.E.; Szabó, I. (European Journal of Obstetrics and Gynecology and Reproductive Biology, 2014)
Objective Previous epidemiological studies have evaluated cases with all congenital heart defects (CHDs), rather than analysing different types of CHD. The objective of this study was to evaluate the possible association of certain chronic maternal diseases with the risk of different types of CHD, because the role of possible environmental factors in the origin of CHDs is unclear in the vast majority of patients. Study design Different types of CHD, diagnosed after lethal outcome (autopsy report) or after surgical intervention (catheter or correction), were evaluated in order to estimate the possible role of chronic maternal diseases in their origin. This analysis was based on the rates of medically recorded chronic maternal diseases in 3562 live-born cases with CHDs, 38,151 population controls without any birth defects, and 16,602 malformed controls with other isolated congenital abnormalities, using the data set of the population-based Hungarian Case-Control Surveillance of Congenital Abnormalities (1980-1996). Results Maternal epilepsy treated with carbamazepine and migraine were found to be associated with higher risk of ventricular septal defect; panic disorders were associated with higher risk of hypoplastic left heart; type I diabetes mellitus was associated with higher risk of coarctation of the aorta; chronic hypertension was associated with higher risk of ventricular septal defect, common atrioventricular canal and common truncus; and paroxysmal supraventricular tachycardia was associated with higher risk of atrial septal defect secundum, common atrioventricular canal and ventricular septal defect. Conclusion In conclusion, certain chronic maternal diseases were found to be associated with higher risk of specific CHDs. Appropriate treatment of these diseases may help to prevent these CHDs.
Keywords: carbamazepine; insulin; phenytoin; valproic acid; adult; aortic coarctation; aortic valve stenosis; article; congenital malformation; cardiovascular risk; chronic disease; congenital heart malformation; controlled study; disease association; Ebstein anomaly; endocardial cushion defect; environmental factor; epilepsy; essential hypertension; Fallot tetralogy; female; great vessels transposition; heart arrhythmia; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; human; human tissue; hypoplastic left heart syndrome; insulin dependent diabetes mellitus; major clinical study; maternal diabetes mellitus; maternal disease; maternal hypertension; migraine; newborn; non insulin dependent diabetes mellitus; panic; paroxysmal supraventricular tachycardia; patent ductus arteriosus; population based case control study; priority journal; pulmonary artery malformation; pulmonary valve atresia; pulmonary valve stenosis; risk assessment; tricuspid valve atresia; tricuspid valve stenosis

First-trimester exposure to bupropion and risk of cardiac malformations - Louik, C.; Kerr, S.; Mitchell, A.A. (Pharmacoepidemiology and Drug Safety, 2014)
Purpose: Bupropion is a drug uniquely used both to treat depression and as an aid to smoking cessation. We investigated previously reported associations between first-trimester exposure to bupropion and cardiac defects. Methods: Using data gathered since 2003 by the Slone Epidemiology Center's Case-control Birth Defects Study, we classified subjects with cardiac defects into subgroups. Exposure categories included first-trimester bupropion alone or in combination with other antidepressants, first-trimester antidepressants other than bupropion, and no exposure to any antidepressant at any time from 2months prior to pregnancy through delivery. We calculated odds ratios and 95% confidence intervals, controlling for confounding using logistic regression. Results: There were 8611 non-malformed infants and 7913 infants with cardiac defects. Eight cardiac subgroups had sufficient subjects (two or more exposed cases) for analysis. The adjusted odds ratio (aOR) for first-trimester bupropion use in relation to ventricular septal defect (VSD) was slightly elevated (1.6, 95% confidence interval 1.0-2.8); for exposure to bupropion alone, the aOR was 2.5 (95% confidence interval 1.3-5.0). Risks were not materially elevated for bupropion in relation to the other seven cardiac subgroups. Conclusions: We did not confirm previously reported associations for left-sided defects overall but had too few exposed cases to evaluate specific defects in this category. We did observe an elevated risk of VSD following first-trimester bupropion use, particularly when used without other antidepressants. This pattern for bupropion alone was observed in all our risk comparisons and was not explained by higher doses or gestational timing.
Keywords: amfebutamone; antidepressant agent; adult; aortic coarctation; article; cardiovascular risk; congenital heart malformation; controlled study; disease association; drug indication; drug safety; female; first trimester pregnancy; heart left ventricle outflow tract obstruction; heart ventricle septum defect; high risk infant; human; hypoplastic left heart syndrome; infant; major clinical study; pregnancy outcome; prenatal drug exposure; risk assessment

Maternal bond with cardiosurgically treated infant. Qualitative analysis of mothers' narratives - Sikora, K.; Janusz, B. (Developmental period medicine, 2014)
The aim of this work is to describe the experience of being a mother by women who together with their children stay on the ward after cardiac surgical correction of congenital heart defects. The research material consisted of the narratives of mothers whose children were born with a heart defect and surgically treated. Four women aged 21-30 years were participants of this study. The age of the subjects' children ranged from 5 weeks to 1 year and three months. The heart defects with which the children were born were hypoplastic left heart syndrome (HLHS ) or atrioventricular canal defect. The research was carried out using the narrative interview. Qualitative analysis was carried out according to the rules of thematic analysis. The results of the research confirm that cardiac treatment can have a significant impact on maternal care patterns and the mother-infant bonding process. Intermittent contact with an infant can lead to loss of control over what happens to the child and the loss of a sense of competence to care for him. Medical staff face the challenge of supporting the parents of hospitalized children in the process of building relationships with a sick infant. The actions of doctors and nurses to enable parents to care for a baby can help foster their sense of competence and responsibility.
Keywords: adaptive behavior; adult; child care; female; congenital heart malformation; heart surgery; human; literature; mother; mother child relation; newborn; object relation; psychology; qualitative research; verbal communication; young adult

Challenges in implementing a pediatric cardiovascular home telehealth project - Black, A.K.; Sadanala, U.K.; Mascio, C.E.; Hornung, C.A.; Keller, B.B. (Telemedicine journal and e-health : the official journal of the American Telemedicine Association, 2014)
OBJECTIVE: Infants with "single ventricle" congenital heart disease are at high risk for sudden death following palliative surgical management. We developed a pilot telemedicine project to evaluate the feasibility of using Web-based daily reporting of clinical data with the goal of reducing unexpected admissions and sudden death. SUBJECTS AND METHODS: We enrolled 9 subjects (enrolled subjects [ES]) following surgical palliation over 12 months. Parents electronically transmitted ES daily weight and oxygen saturation and then completed an automated 10-point phone questionnaire on nutrition, activity, and distress. Subject enrollment continued until a second surgical palliative procedure (n=5), sudden death (n=2), or disenrollment (n=2). We collected clinical data on all ES and 9 historical controls (HC) from the preceding 18 months and analyzed clinical management, including outpatient telephone surveillance success, scheduled and unscheduled office and emergency department visits, hospitalizations, procedures, and adverse events, including death. RESULTS: Subject recruitment was more difficult than expected. Weight transmission success was high, but there was poor correlation between telemedicine system-measured oxygen saturation and a commercial monitor. The outpatient clinical telephone surveillance success rate for HC and ES was approximately 30%. After technical adjustments, parents of all ES (100%) were able to transmit questionnaire data. There were 9 emergency room visits for ES versus 11 unscheduled emergency room visits for HC. Sudden death occurred in 1 of 9 HC and 2 of 9 ES. CONCLUSIONS: Telemedicine monitoring for high-risk congenital heart disease patients is feasible but challenging, may reduce unscheduled visits, but may not impact the primary end point of preventing sudden death in this high-risk pediatric population.
Keywords: oxygen; blood; body weight; cardiology; emergency health service; feasibility study; female; congenital heart malformation; home care; human; infant; Internet; male; mortality; newborn; organization and management; palliative therapy; pediatrics; physiologic monitoring; pilot study; procedures; questionnaire; sudden cardiac death; telemedicine; utilization

Parental Mental Health Moderates the Efficacy of Exercise Training on Health-Related Quality of Life in Adolescents with Congenital Heart Disease - Dulfer, K.; Duppen, N.; Van Dijk, A.P.J.; Kuipers, I.M.; Van Domburg, R.T.; Verhulst, F.C.; Van der Ende, J.; Helbing, W.A.; Utens, E.M.W.J. (Pediatric Cardiology, 2014)
To evaluate the moderating influence of parental variables on changes in health-related quality of life (HRQoL) in adolescents with Tetralogy of Fallot (ToF) or a Fontan circulation after participation in standardized exercise training. A multicenter randomized controlled trail in which 56 patients, aged 10-15, were randomly allocated (stratified by age, gender, and congenital heart disease) to a 12-week period with either: (a) 3 times per week standardized exercise training or (b) care-as-usual (randomization ratio 2:1). Adolescents and their parents filled in online questionnaires at baseline and at 12-week follow-up. In this randomized controlled trail, primary analyses involved influence of parental mental health and parental social support for exercise on changes in the TNO/AZL Child Quality of Life Questionnaire Child Form at follow-up. Secondary analyses concerned comparing levels of parental characteristics with normative data. Compared with controls, adolescents in the exercise group reported a decrease in social functioning when their parents had more anxiety/insomnia or severe depression themselves. Adolescents also reported a decrease in social functioning when their parents showed poorer overall mental health themselves. Parents reported comparable or even better mental health compared with normative data. The effect of a standardized exercise program on HRQoL changes in adolescents with ToF or a Fontan circulation is moderated by parental mental health, more specifically by parental anxiety/insomnia and severe depression. The trial registration number of this article is NTR2731 (www.trialregister.nl). © 2014 Springer Science+Business Media New York.
Keywords: human; adolescent; congenital heart malformation; mental health; parent; congenital heart disease; exercise; quality of life; child; aerobic exercise; follow up; questionnaire; social interaction; social support; randomization; gender; patient; Fallot tetralogy; commercial phenomena; registration; secondary analysis; United States

Follow-up of congenital heart disease patients with subclinical hypothyroidism - Martínez-Quintana, E.; Rodríguez-González, F. (Cardiology in the Young, 2015)
Introduction: Subclinical hypothyroidism or mild thyroid failure is a common problem in patients without known thyroid disease. Methods: Demographic and analytical data were collected in 309, of which 181 were Male and 128 were feMale, congenital heart disease (CHD) patients. CHD patients with thyroid-stimulating hormone above 5.5 mIU/L were also followed up from an analytical point of view to determine changes in serum glucose, cholesterol, N-terminal pro b-type natriuretic peptide, and C-reactive protein concentrations. Results: Of the CHD patients, 35 (11.3%) showed thyroid-stimulating hormone concentration above 5.5 mIU/L. Of them, 27 were followed up during 2.4±1.2 years - 10 were under thyroid hormone replacement treatment, and 17 were not. Of the 27 patients (25.9%), 7 with subclinical hypothyroidism had positive anti-thyroid peroxidase, and 3 of them (42.8%) with positive anti-thyroid peroxidase had Down syndrome. Down syndrome and hypoxaemic CHD patients showed higher thyroid-stimulating hormone concentrations than the rest of the congenital patients (p<0.001). No significant differences were observed in serum thyroxine, creatinine, uric acid, lipids, C-reactive protein, or N-terminal pro b-type natriuretic peptide concentrations before and after the follow-up in those CHD patients with thyroid-stimulating hormone above 5.5 mIU/L whether or not they received levothyroxine therapy. Conclusions: CHD patients with subclinical hypothyroidism showed no significant changes in serum thyroxine, cholesterol, C-reactive protein, or N-terminal pro b-type natriuretic peptide concentrations whether or not they were treated with thyroid hormone replacement therapy.
Keywords: amino terminal pro brain natriuretic peptide; C reactive protein; cholesterol; creatinine; glucose; high density lipoprotein cholesterol; levothyroxine; low density lipoprotein cholesterol; thyroid peroxidase antibody; thyrotropin; uric acid; adolescent; adult; aged; aortic coarctation; aortic stenosis; article; atrioventricular septal defect; bicuspid aortic valve; cholesterol blood level; congenital heart disease; creatinine blood level; Down syndrome; Fallot tetralogy; female; follow up; glucose blood level; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; hormone substitution; human; major clinical study; male; protein blood level; pulmonary valve atresia; pulmonary valve stenosis; sex difference; subclinical hypothyroidism; thyrotropin blood level; uric acid blood level; very elderly

Psychosocial responses of parents to their infant's diagnosis of hypoplastic left heart syndrome - Cantwell-Bartl, A.M.; Tibballs, J. (Cardiology in the Young, 2015)
Objective: To evaluate the psychosocial status of mothers and fathers in response to their infant's diagnosis of hypoplastic left heart syndrome. Design: A study on interviews with parents whose children had survived staged surgery. Setting: Tertiary hospital paediatric ICU. Subjects: A total of 29 parents (16 mothers and 13 fathers) of surviving children. Intervention: A semi-structured face-to-face interview was conducted to explore experiences of parents in response to their infant's diagnosis, their interaction with the doctor delivering the diagnosis, their deliberation about staged surgery, and their reasons for this choice. Measurement and Main Results: All parents were devastated about their infant's diagnosis, and most (83%) of them said that the time of the diagnosis and the aftermath was the worst time of their lives. Parents reported helpful and unhelpful communication at this time. Although all parents in this study chose surgery for their infant, when faced with the choice, 17 of them made an immediate decision to protect their infant's life, 8 were initially unsure when their infant was diagnosed in utero, and 4 were unsure when the infant was diagnosed after birth. Parents also experienced loss and other stressors. Conclusions: All parents of the infants diagnosed with hypoplastic left heart syndrome experienced intense loss and stressors. Physicians need to be sensitive to the needs and thinking of the parents when discussing treatment options before surgery. The nature of the relationship with the doctor at this time can support parents or be a further source of stress.
Keywords: article; controlled study; family decision making; female; human; hypoplastic left heart syndrome; infant; interpersonal communication; male; maternal behavior; mental stress; paternal behavior; personal experience; social psychology

Array comparative genomic hybridisation testing in CHD - Hightower, H.B.; Robin, N.H.; Mikhail, F.M.; Ambalavanan, N. (Cardiology in the Young, 2015)
Background: CHD is the leading cause of mortality due to birth defects. Array comparative genomic hybridisation (aCGH) detects submicroscopic copy number changes and may improve identification of the genetic basis of CHD. Methods: This is a retrospective analysis of 1252 patients from a regional referral centre who had undergone aCGH. Of the patients, 173 had CHD. A whole-genome custom-designed oligonucleotide array with >44,000 probes was used to detect copy number changes. Results: Of the 1252 patients, 335 (26.76%) had abnormal aCGH results. Of the 173 patients with CHD, 50 (28.9%) had abnormal aCGH results versus 284 (26.3%) of 1079 non-cardiac patients. There were six patients with CHD who had well-described syndromes such as Wolf-Hirschhorn, trisomy 13, DiGeorge, and Williams. Of the patients with CHD, those with left-sided heart disease had the highest proportion (14/31; 45.13%) of abnormal aCGH results, followed by those with conotruncal heart disease (10/29; 34.48%), endocardial cushion defects (13/50; 26%), complex/other heart disease (12/52; 23.08%), and patent ductus arteriosus (1/11; 9.09%). Conclusions: Patients with CHD are at a substantial risk of having microdeletions and microduplications. The incidence of abnormalities on aCGH analysis is higher than identified with karyotype, and identification of copy number changes may help identify the genetic basis of the specific heart defects. However, aCGH may not have a significant diagnostic yield in those with isolated CHD. Further research using larger data sets may help identify candidate genes associated with CHD.
Keywords: left right determination factor; protein Nodal; transcription factor GATA 4; transcription factor GATA 6; aortic arch interruption; aortic coarctation; aortic valve disease; array comparative genomic hybridization; article; chromosome deletion; chromosome deletion 15q11; chromosome deletion 22q11; comparative genomic hybridization; congenital heart malformation; controlled study; copy number variation; CRELD1 gene; DiGeorge syndrome; DNA microarray; endocardial cushion defect; Fallot tetralogy; GATA4 gene; GATA6 gene; gene; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; human; hypoplastic left heart syndrome; infant; karyotype; LEFTY gene; lung vein drainage anomaly; major clinical study; male; NKX25 gene; NODAL gene; patent ductus arteriosus; pulmonary valve atresia; retrospective study; TBX20 gene; trisomy 13; Williams Beuren syndrome; Wolf Hirschhorn syndrome; ZIC3 gene

A young child with bilateral diaphragmatic palsy after bilateral bidirectional Glenn shunt - Shamsuddin, A.K.; Biswas, S.K.; Rahman, M.Z.; Biswas, S.; Hasan, N.A.; Sharifuzzaman, M. (Mymensingh medical journal : MMJ, 2014)
A 13-months old boy was admitted in National Heart Foundation Hospital and Research Institute on 3 August 2011 with the diagnosis of Dextrocardia, A-V discordance, DORV, large perimembranous VSD, severe infundibular and valvular PS, bilateral SVC. He was operated on 10 August 2011. Bilateral bidirectional Glenn shunt was done off pump along with interruption of PDA. Antegrade pulmonary blood flow was minimized by tight PA banding. Baby was extubated 3 hours after surgery but had to reintubate immediately due to intense respiratory distress. Subsequent three trials of extubation failed. Chest x-ray revealed elevation of both the hemidiaphragm. Ultrasonogram of abdomen and Bronchogram along with fluoroscopy done and bilateral diaphragmatic palsy was diagnosed. Tracheostomy was done on 25th August 2011. Plication of left hemidiaphragm was done on 27th August and right hemidiaphragm plication was done on 10th September 2011. Though it took long period of time we managed to take him out of ventilator on 57th postoperative day. He was oxygen dependent for a period of time and finally he managed to take his own breath without tracheostomy tube from 67th postoperative day. After a long eventful postoperative hospital stay he was discharged home on 78th postoperative day. Discharge Chest x-ray revealed well expanded lung with flattened diaphragm. Echo revealed well functioning bilateral Glenn shunt. Tracheostomy wound healed nicely and there was no evidence of tracheal stenosis.
Keywords: case report; Fontan procedure; human; infant; male; diaphragm paralysis

Health-related quality of life outcomes in children and adolescents with congenital heart disease - Mellion, K.; Uzark, K.; Cassedy, A.; Drotar, D.; Wernovsky, G.; Newburger, J.W.; Mahony, L.; Mussatto, K.; Cohen, M.; Limbers, C.; Marino, B.S. (Journal of Pediatrics, 2014)
Objectives To compare health-related quality of life (HRQOL) in a group of pediatric patients with congenital heart disease (CHD) and healthy controls and patients with other chronic diseases, and to compare HRQOL among patients with CHD of various severity categories with one another, with controls, and with patients with other chronic diseases. Study design In this cross-sectional survey, t tests were used to compare patient and proxy-reported Pediatric Quality of Life Inventory 4.0 Generic Core Scales (PedsQL) scores (including total, physical health, and psychosocial health summary scores) in children (aged 8-12 years) and adolescents (aged 13-18 years) between controls and (1) a composite CHD population; and (2) patients in each of 3 CHD severity categories: mild (no intervention), biventricle (BV; postintervention), and single ventricle (SV; postpalliation). PedsQL scores among CHD severity categories were compared by ANOVA. PedsQL scores were also compared in the CHD population and children with other chronic diseases without age stratification using t tests. Results There were 1138 (children, n = 625; adolescents, n = 513) and 771 (children, n = 528; adolescents, n = 243) patient and/or proxy reporters in the CHD and healthy control groups, respectively. Total, physical health, and psychosocial health summary scores were lower in the composite CHD, BV, and SV groups compared with controls (P <.0001). There were significant differences among disease severity categories for all scores (P <.01). The composite CHD, BV, and SV groups had similar PedsQL scores as end-stage renal disease, asthma, and obesity populations. Conclusion Children and adolescents with BV and SV CHD have significantly lower HRQOL than healthy controls and similar HRQOL as patients with other chronic pediatric diseases. Interventions targeting both physical and psychosocial domains are needed to improve HRQOL in this high-risk population. © 2014 Mosby Inc. All rights reserved.
Keywords: adolescent; article; asthma; child; chronic disease; congenital heart disease; controlled study; disease severity; end stage renal disease; female; heart single ventricle; human; major clinical study; male; obesity; Pediatric Quality of Life Inventory 4.0 Generic Core Scale; priority journal; quality of life; school child; scoring system; Student t test

Prevalence of arrhythmias late after the fontan operation - Lasa, J.J.; Glatz, A.C.; Daga, A.; Shah, M. (American Journal of Cardiology, 2014)
The extracardiac conduit (ECC) modification of the Fontan procedure has been theorized to reduce the risk of sinus node dysfunction and atrial arrhythmia compared with the intraatrial lateral tunnel (ILT) Fontan. This study aimed to compare the prevalence of early and late arrhythmias in patients who underwent ECC and ILT Fontan from a similar era with long-term follow-up at a single institution. A retrospective cohort study was conducted of all patients who underwent ECC or ILT Fontan from 1995 to 2005 at The Children's Hospital of Philadelphia. Bradyarrhythmias (including sinus node dysfunction), tachyarrhythmias, and pacemaker burden prevalence was determined throughout early (<30 days) and late (>30 days) postoperative periods. Of 434 patients undergoing the Fontan procedure during the study period, a total of 87 and 106 patients who underwent ECC and ILT Fontan, respectively, met the inclusion criteria. There were no significant differences in risk of sinus node dysfunction or tachyarrhythmia in both early and late postoperative periods. Although the overall risk of late postoperative pacemaker therapy was lower for the ECC cohort (4.9% vs 15.7%, p = 0.03), when adjusting for follow-up time, no significant difference was observed (odds ratio 3.1, 95% confidence interval 0.6 to 15.2, p = 0.16). In conclusion, the overall prevalence of late postoperative arrhythmias observed after contemporary Fontan modifications is low. Intra-atrial reentrant tachycardia, a potentially fatal complication of the atriopulmonary Fontan operation was infrequently encountered in both ECC and ILT Fontan cohorts. Pacemaker use was higher in the ILT group, although this difference may be explained by differences in follow-up time. Despite the low prevalence of arrhythmias after contemporary Fontan modifications, ongoing surveillance is warranted as the onset of arrhythmias may emerge after longer follow-up time. © 2014 Elsevier Inc. All rights reserved.
Keywords: article; atriopulmonary connection; bradycardia; cardiovascular risk; cavopulmonary connection; child; cohort analysis; comparative study; complete heart block; extracardiac conduit; female; follow up; Fontan procedure; heart arrhythmia; heart atrium arrhythmia; heart transplantation; heart ventricle tachycardia; Holter monitoring; human; implanted heart pacemaker; intraatrial lateral tunnel; junctional ectopic tachycardia; major clinical study; male; medical record review; postoperative period; prevalence; priority journal; retrospective study; risk reduction; school child; sinoatrial nodal reentry tachycardia; sinus node disease; surgical technique; tachycardia; univariate analysis

Management of plastic bronchitis with nebulized tissue plasminogen activator: Another brick in the wall - Colaneri, M.; Quarti, A.; Pozzi, M.; Gasparini, S.; Carloni, I.; De Benedictis, F.M. (Italian Journal of Pediatrics, 2014)
Plastic bronchitis is a rare complication of a variety of respiratory diseases and congenital heart disease surgery, particularly Fontan procedure. Bronchial casts with rubber-like consistency develop acutely and may cause severe life-threatening respiratory distress. The management of plastic bronchitis is yet not well defined. Early intermittent, self-administered nebulization of tissue plasminogen activator was found to be effective in preventing deterioration of acute respiratory symptoms in a patient with primary ciliary dyskinesia and recurrent cast formation. Further investigation into new therapeutic strategies for this devastating disease is advocated. © 2014 Colaneri et al.; licensee BioMed Central Ltd.
Keywords: acetylcysteine; epinephrine; alteplase; antiasthmatic agent; antibiotic agent; budesonide; deoxyribonuclease; dopamine; enoximone; fibrin; salbutamol; sildenafil; sodium chloride; abnormal respiratory sound; absence of side effects; adolescent; article; artificial ventilation; asplenia; atelectasis; atrial isomerism; atrioventricular block; breathing exercise; bronchitis; bronchus secretion; case report; chronic lung disease; chronic oto sino pulmonary disease; ciliary dyskinesia; congenital heart disease; continuous hemofiltration; coughing; croupous bronchitis; deterioration; drug efficacy; lack of drug effect; dyspnea; echocardiography; electron microscopy; fever; fiberoptic bronchoscopy; fibrinolytic therapy; follow up; Fontan procedure; forward heart failure; Glenn shunt; great vessels transposition; heart catheterization; heart dilatation; heart disease; heart ejection fraction; heart right ventricle double outlet; heart ventricle septum defect; histopathology; hospital admission; hospital discharge; human; human tissue; inferior cava vein; inflammatory cell; intensive care unit; lung auscultation; lung resistance; male; mechanical chest compressor; medical history; multiple organ failure; nebulization; nebulizer; oxygen mask; physical examination; pleura effusion; postoperative complication; pulmonary artery stenosis; recurrent disease; repeated drug dose; respiratory distress; superior cava vein; thorax pain; thorax radiography; tracheobronchial tree; ultrafiltration; wheezing; actilyse; Pari LC Sprint; Pari TurboBoy S compressor

How not to tell parents about their child's new diagnosis of congenital heart disease: An internet survey of 841 parents - Hilton-Kamm, D.; Sklansky, M.; Chang, R.-K. (Pediatric Cardiology, 2014)
An online survey for parents of children with congenital heart disease (CHD) was developed to study the perceptions and experiences of parents when receiving the diagnosis. The survey was distributed to online support groups. A total of 841 responses from parents of children with CHD in the United States were received over a 4-week period in 2010. The authors hypothesized that the counseling and demeanor of the pediatric cardiologist (PC) may be important factors in determining whether parents of children with CHD seek second opinions, and that the terminology used in counseling may be variably interpreted. Of the 841 respondents, 349 (41 %) received the diagnosis prenatally. A minority of the respondents received: support group information (14 %), Internet resources (21 %), success rates at other hospitals (16 %), or maximum ages of survivors (29 %). Among 26 % of the parents who reported seeking a second opinion from another PC, the majority (71 %) chose the second PC for long-term follow-up care. Those receiving a prenatal diagnosis were more likely to seek a second opinion than those receiving the diagnosis postnatally (32 vs 22 %; p < 0.01). Parents' perception of the PC's compassion and empathy was inversely related to the likelihood of seeking a second opinion. Parents were more likely to seek a second opinion when they were not optimistic about their child's life expectancy, felt pressured by the PC to terminate the pregnancy, were told that their child's death was "somewhat" or "very" likely, or were told the child's CHD was "rare" (all p < 0.01). Two thirds (66 %) of the respondents were told that their child's condition was "rare." The majority of these (77 %) reported that the term was used by the PC. "Rare" was interpreted as "occurring in less than a million births" by 25 %, and as "few or no other people alive with this defect" by 27 %. Parental interpretation of "rare" was unrelated to their levels of education. As reported by the respondents, 13 % felt pressured to terminate the pregnancy by the PC. Those with hypoplastic left heart syndrome were more likely to report feeling pressure to terminate the pregnancy by the PC (21 vs 9 %; p < 0.001) or the perinatologist (23 vs 14 %; p = 0.026). The approach to counseling and the demeanor of the PC have important implications for parents' perceptions of their child's chance of survival. The information given at diagnosis, the manner in which it is presented, and the parents' understanding and interpretation of that information are critical factors in shaping parents' perceptions and management decisions. © 2013 Springer Science+Business Media New York.
Keywords: adult; age distribution; article; birth; child death; childhood disease; congenital heart disease; doctor patient relationship; educational status; empathy; female; follow up; health survey; human; human experiment; hypoplastic left heart syndrome; Internet; life expectancy; long term care; male; medical information; medical terminology; optimism; parent; parent counseling; pediatric cardiology; perception; perinatal period; personal experience; physician attitude; pregnancy termination; prenatal diagnosis; support group; survivor; United States

Feeding dysfunction in children with single ventricle following staged palliation - Hill, G.D.; Silverman, A.H.; Noel, R.J.; Simpson, P.M.; Slicker, J.; Scott, A.E.; Bartz, P.J. (Journal of Pediatrics, 2014)
Objective To determine the prevalence of feeding dysfunction in children with single ventricle defects and identify associated risk factors. Study design Patients aged 2-6 years with single ventricle physiology presenting for routine cardiology follow-up at the Children's Hospital of Wisconsin were prospectively identified. Parents of the patients completed 2 validated instruments for assessment of feeding dysfunction. Chart review was performed to retrospectively obtain demographic and diagnostic data. Results Instruments were completed for 56 patients; median age was 39 months. Overall, 28 (50%) patients had some form of feeding dysfunction. Compared with a normal reference population, patients with single ventricle had statistically significant differences in dysfunctional food manipulation (P <.001), mealtime aggression (P =.002), choking/gagging/vomiting (P <.001), resistance to eating (P <.001), and parental aversion to mealtime (P <.001). Weight and height for age z-scores were significantly lower in subjects with feeding dysfunction (-0.84 vs -0.33; P <.05 and -1.46 vs -0.56; P =.001, respectively). Multivariable analysis identified current gastrostomy tube use (P =.02) and a single parent household (P =.01) as risk factors for feeding dysfunction. Conclusion Feeding dysfunction is common in children with single ventricle defects, occurring in 50% of our cohort. Feeding dysfunction is associated with worse growth measures. Current gastrostomy tube use and a single parent household were identified as independent risk factors for feeding dysfunction.
Keywords: airway obstruction; article; child; childhood disease; controlled study; disease association; feeding disorder; female; follow up; food aversion; gastrointestinal symptom; heart single ventricle; height; household; human; major clinical study; male; medical record review; palliative therapy; preschool child; prevalence; priority journal; prospective study; risk factor; single parent; stomach tube; vomiting; weight

Risk and prevalence of developmental delay in young children with congenital heart disease - Mussatto, K.A.; Hoffmann, R.G.; Hoffman, G.M.; Tweddell, J.S.; Bear, L.; Cao, Y.; Brosig, C. (Pediatrics, 2014)
BACKGROUND AND OBJECTIVE: Children with congenital heart disease (CHD) are at risk for developmental delay (DD). Changes in cognitive, language, and motor skills in early childhood have not been described. We report the results of a structured approach using longitudinal testing to identify problems and ensure early intervention in accordance with published guidelines. METHODS: Bayley Scales of Infant Development, Third Edition, were used to assess cognitive, language, and motor skills in 99 children with CHD. Subjects were evaluated 3 to 6 times in the first 3 years of life. DD was defined as scores >1 SD below the population mean. RESULTS: Cardiac anatomy was single ventricle (1V) in 34 subjects and 2 ventricles (2V) in 65. Medical comorbidities were present in 21% and genetic syndromes in 19%. Most subjects (75%) had DD in ≥1 area at ≥1 assessments. Subjects with 1V anatomy had equivalent outcomes to those with 2V. Cognitive and language scores declined in subjects with genetic syndromes but were stable and within the average range for subjects with 1V and 2V. Motor scores improved for subjects with 1V and 2V but remained low for those with genetic syndromes. In addition to age, need for supplemental tube feeding, longer cardiopulmonary bypass time, and shorter time since last hospitalization were significant predictors of developmental outcomes. CONCLUSIONS: DDs in young children with CHD are both common and dynamic. Providers should encourage longitudinal surveillance for children with CHD because exposure to risk and prevalence of DD change over time. Copyright © 2014 by the American Academy of Pediatrics.
Keywords: age; article; Bayley Scales of Infant Development; cardiopulmonary bypass; child; cognition; comorbidity; congenital heart disease; developmental disorder; enteric feeding; female; genetic disorder; heart single ventricle; hospitalization; human; language; major clinical study; male; motor performance; outcome assessment; practice guideline; preschool child; prevalence; priority journal; risk assessment; risk factor; scoring system

The relationship of patient medical and laboratory characteristics to changes in functional health status in children and adolescents after the Fontan procedure - McCrindle, B.W.; Zak, V.; Breitbart, R.E.; Mahony, L.; Shrader, P.; Lai, W.W.; Burns, K.M.; Colan, S.D.; Williams, R.V.; Goldberg, D.; Hill, K.D.; Khaikin, S.; et al. (Pediatric Cardiology, 2014)
Despite hypothesized concerns about deterioration beginning in adolescence, longitudinal data and associated factors regarding standardized assessment of physical functioning are not available for Fontan patients. Parents who participated in the Fontan Cross-Sectional Study completed the Child Health Questionnaire at 2 time points for 245 subjects ages 6-18 years. Associations between change in Physical Functioning Summary Score and baseline patient, medical, and laboratory characteristics (mean age 9.5 ± 1.7 years) and follow-up patient and medical characteristics (mean age 16.2 ± 1.6 years) were determined by regression analyses. During a mean of 6.7 ± 0.4 years, a small (not clinically important) but statistically significant decrease in score from 46.2 ± 11.7 to 44.5 ± 12.1 (p < 0.03) was noted. Subjects with higher baseline scores had a greater decrease in score (r = -0.48; p < 0.001). A multivariable model of patient and medical characteristics (R2 = 0.11) showed that a greater decrease in score was significantly associated with interim development of asthma (n = 13; parameter estimate [PE] -6.6; p < 0.05) or other chronic respiratory, lung, or breathing problems (n = 13; PE -12.5; p < 0.001) and the presence of protein-losing enteropathy at any time (n = 12; PE -9.4; p = 0.006). Change in score was not significantly associated with baseline laboratory measures of exercise capacity and ventricular characteristics and function. Therefore, although physical functioning may be stable during adolescence for many Fontan patients, deterioration occurs in some in association with respiratory conditions and protein-losing enteropathy. Further longitudinal study is necessary to better understand the relationship between clinical morbidities and functional health status as these patients transition into adulthood. © 2013 Springer Science+Business Media.
Keywords: adolescent; adolescent health; adult; article; breathing; cavopulmonary connection; child; child health; cross-sectional study; echocardiography; exercise; exercise test; female; follow up; Fontan procedure; health status; heart function; human; longitudinal study; major clinical study; male; morbidity; nuclear magnetic resonance imaging; physical performance; preschool child; protein losing gastroenteropathy; quality of life; questionnaire; school child; social psychology; social status; young adult

Successful noninvasive mechanical ventilation in a child on prolonged and life-threatening invasive mechanical ventilation after Fontan operation - Yaman, A.; Kendirli, T.; Ödek, C.; Karadeniz, C.; Uçar, T.; Göllü, G.; Eyileten, Z.; Ince, E. (Turkish Journal of Pediatrics, 2014)
For many decades, the primary treatment of acute respiratory failure has been mechanical ventilation. Intubation and mechanical ventilation carry complications such as upper respiratory system trauma, barotrauma, volutrauma, oxytrauma, atelectrauma, and nosocomial infection, and they increase mortality. Noninvasive mechanical ventilation (NIMV) applied to a specially selected group of patients has more advantages than invasive ventilation, especially the decreased number of complications. We present a three-year-old girl who had prolonged invasive mechanical ventilation (IMV) and weaning failure due to severe tracheal bleeding after Fontan operation. She could not be extubated for 20 days after admission to our Pediatric Intensive Care Unit (PICU) because of life-threatening airway bleedings from within the endotracheal tube. Owing to the severe bleedings during endotracheal aspirations, it was decided to change her mechanical ventilation to NIMV. NIMV was performed successfully for 12 days without difficulty, and she was discharged from the hospital on the 55th postoperative day with normal clinical findings. Noninvasive ventilation has an increasing use in critically ill children. NIMV should be considered in prolonged mechanical ventilation and weaning failure from IMV in critically ill children.
Keywords: epinephrine; argon; dopamine; fresh frozen plasma; heparin; milrinone; protamine sulfate; acute respiratory failure; article; artificial ventilation; assisted ventilation; bleeding tendency; blood analysis; bronchoscopy; case report; child; drug megadose; edema; endotracheal intubation; endotracheal tube; female; Fontan procedure; human; hyperemia; hypotension; hypoxia; intubation; liver function test; lung hemorrhage; mortality; noninvasive ventilation; peak expiratory flow; peak inspiratory flow; positive pressure ventilation; preschool child; prothrombin time; thorax radiography; tracheal hemorrhage; weaning

Prenatal diagnosis of multiple fetal anomalies in naphthalene-addicted pregnant women: A case report - Boynukalin, F.K.; Baykal, C. (Clinical and Experimental Obstetrics and Gynecology, 2014)
Background: Naphthalene is one of the abused inhalants. It has been associated with acute and chronic health problems. To the authors' knowledge, prenatal exposure to naphthalene has never been discussed in humans. Case: The authors discuss a case of naphthalene-addicted pregnant women with multiple fetal anomalies. At 15 weeks gestation, ultrasound screening demostrated multiple fetal anomalies: anencephaly, scoliosis, diffuse subcutaneous edema, flexion contracture of lower extremities, and hypoplastic left ventricle. Four weeks later obstetrical ultrasonography revealed that there was no fetal cardiac activity. The patient had a medical abortion. Conclusion: A stronger knowledge basis regarding naphthalene-related fetal anomaly is required to ensure accurate direct link, however the probability of naphthalene-related fetal anomaly must be considered.
Keywords: naphthalene; adult; anencephalus; article; autopsy; case report; crown rump length; drug dependence; edema; female; fetus; fetus echography; fetus malformation; flexion contracture; gestational age; heart left ventricle; human; hypoplastic left heart syndrome; leg; medical abortion; menstrual cycle; multiple malformation syndrome; nausea and vomiting; physical examination; pleura effusion; pregnant woman; prenatal diagnosis; prenatal drug exposure; scoliosis; young adult

Functional health status in children and adolescents after Fontan: Comparison of generic and disease-specific assessments - Mccrindle, B.W.; Zak, V.; Pemberton, V.L.; Lambert, L.M.; Vetter, V.L.; Lai, W.W.; Uzark, K.; Margossian, R.; Atz, A.M.; Cook, A.; Newburger, J.W. (Cardiology in the Young, 2014)
Purpose: The aim of this study was to compare associations between generic versus disease-specific functional health status assessments and patient and clinical characteristics for patients with severe congenital heart disease. Methods: This was a cross-sectional observational study involving 325 single ventricle patients, aged 10-18 years, after Fontan procedure. Enrolled patients underwent a medical history review, laboratory testing, and assessment of the functional health status by completion of the generic Child Report Child Health Questionnaire and the disease-specific Congenital Heart Adolescent and Teenage questionnaire. Correlated conceptually equivalent domains from both questionnaires were identified and their associations with patient and clinical variables were compared. Results: From the generic assessment, patients perceived marginally lower physical functioning (p = 0.05) but greater freedom from bodily pain compared with a normal population (p < 0.001). The equivalent physical functioning/limitations domain of the generic instrument, compared with the disease-specific instrument, had similar associations (higher multi-variable model R2) with medical history variables (R 2 = 0.14 versus R2 = 0.12, respectively) and stronger associations with exercise testing variables (R2 = 0.22 versus R 2 = 0.06). Similarly, the corresponding freedom from bodily pain/symptoms domains from both questionnaires showed a greater association for the generic instrument with medical history variables (R2 = 0.15 versus R2 = 0.09, respectively) and non-cardiac conditions (R 2 = 0.13 versus R2 = 0.06). The associations of each questionnaire with echocardiographic results, cardiac magnetic resonance imaging results, and serum brain natriuretic peptide levels were uniformly weak (R 2 range <0.01 to 0.04). Conclusions: Assessment of the physical functional health status using generic and disease-specific instruments yields few differences with regard to associations between conceptually similar domains and patient and clinical characteristics for adolescents after Fontan procedure. © Cambridge University Press 2013.
Keywords: brain natriuretic peptide; adolescent; adult; article; cardiovascular magnetic resonance; child; child health; Child Health Questionnaire; clinical assessment; Congenital Heart Adolescent and Teenage questionnaire; congenital heart disease; controlled study; cross-sectional study; echocardiography; exercise test; female; Fontan procedure; functional status; hormone blood level; human; intermethod comparison; major clinical study; male; medical history; assessment of humans; observational study; pain; Parent Report Child Health Questionnaire; patient assessment; Physical and Psychosocial Functioning Summary Score; physical capacity; quality of life; school child; scoring system

One and a half ventricle repair in association with tricuspid valve repair according to "peacock tail" technique in patients with ebstein's malformation and failing right ventricle - Prifti, E.; Baboci, A.; Esposito, G.; Kajo, E.; Dado, E.; Vanini, V. (Journal of Cardiac Surgery, 2014)
Objectives The aim of this study was to evaluate the outcome in a series of patients with Ebstein's anomaly and a failing right ventricle (RV) undergoing tricuspid valve (TV) repair and bidirectional Glenn cavopulmonary anastomosis (BDG). Materials and Method Between January 2006 and September 2013, 11 consecutive patients diagnosed with severe forms of Ebstein's anomaly and a failing RV underwent TV surgery and BDG. The mean age was 16.5 ± 7 years. Most frequently found symptoms were cyanosis, dyspnea, and arrhythmias. The azygos or hemiazygos veins were left open. The TV was repaired using the "peacock tail" technique, which consisted of total detachment of the anterior and posterior leaflets of the TV and rotation in both directions reimplanting them to the true annulus. The mean follow-up was 3.8 ± 2.4 years (range three months to six years). Results Hospital mortality was 9% (one patient). TV repair was possible in 10 patients. None of the patients had AV block postoperatively. At one year after surgery, the indexed RV and RA diameter were reduced significantly versus the preoperative data (p = 0.003 and p < 0.001). The mean TVR and indexed TV area were 1.2 ± 0.42 and 1.6 ± 0.6 (mm/m2), significantly lower than preoperatively (p = 0.001 and p = 0.008, respectively). The mean NYHA functional class, SaO2, and cardiothoracic ratio were significantly improved. Conclusions The peacock tail technique for TV repair in combination with BDG in patients with Ebstein's malformation and depressed RV function results in TV preservation, a low incidence of recurrent regurgitation, favorable functional status and RV function, and resolution of cyanosis. © 2013 Wiley Periodicals, Inc.
Keywords: adolescent; article; azygos vein; cavopulmonary connection; child; complete heart block; cyanosis; disease severity; dyspnea; Ebstein anomaly; echocardiography; epicardial pacemaker; female; follow up; Fontan procedure; heart arrhythmia; heart right ventricle failure; heart ventricle septum defect; hemiazygos vein; human; major clinical study; male; mortality; New York Heart Association class; outcome assessment; peacock tail technique; postoperative period; pulmonary valve stenosis; reimplantation; tricuspid valve prosthesis; tricuspid valve repair; vein; Epic

Social media methods for studying rare diseases - Schumacher, K.R.; Stringer, K.A.; Donohue, J.E.; Yu, S.; Shaver, A.; Caruthers, R.L.; Zikmund-Fisher, B.J.; Fifer, C.; Goldberg, C.; Russell, M.W. (Pediatrics, 2014)
For pediatric rare diseases, the number of patients available to support traditional research methods is often inadequate. However, patients who have similar diseases cluster "virtually" online via social media. This study aimed to (1) determine whether patients who have the rare diseases Fontan-associated protein losing enteropathy (PLE) and plastic bronchitis (PB) would participate in online research, and (2) explore response patterns to examine social media's role in participation compared with other referral modalities. A novel, internetbased survey querying details of potential pathogenesis, course, and treatment of PLE and PB was created. The study was available online via web and Facebook portals for 1 year. Apart from 2 study-initiated posts on patient-run Facebook pages at the study initiation, all recruitment was driven by study respondents only. Response patterns and referral sources were tracked. A total of 671 respondents with a Fontan palliation completed a valid survey, including 76 who had PLE and 46 who had PB. Responses over time demonstrated periodic, marked increases as new online populations of Fontan patients were reached. Of the responses, 574 (86%) were from the United States and 97 (14%) were international. The leading referral sources were Facebook, internet forums, and traditional websites. Overall, social media outlets referred 84% of all responses, making it the dominant modality for recruiting the largest reported contemporary cohort of Fontan patients and patients who have PLE and PB. The methodology and response patterns from this study can be used to design research applications for other rare diseases. Copyright © 2014 by the American Academy of Pediatrics.
Keywords: access to information; African American; article; Asian; bronchitis; Caucasian; child; childhood disease; cohort analysis; comparative study; controlled study; croupous bronchitis; feasibility study; female; Fontan procedure; geographic distribution; health survey; Hispanic; human; Internet; major clinical study; male; medical research; online system; Pacific Islander; patient attitude; patient history of surgery; patient participation; patient referral; priority journal; protein losing gastroenteropathy; rare disease; self report; social media; social network; study design; United States; validation process

Transthoracic echocardiographic predictors of left atrial hypertension in patients on venoarterial extracorporeal membrane oxygenation - Eckhauser, A.W.; Jones, C.; Witte, M.K.; Puchalski, M.D. (World Journal for Pediatric and Congenital Heart Surgery, 2014)
Decompression of the left heart in patients supported with extracorporeal membrane oxygenation (ECMO) is often warranted to protect the myocardium and facilitate recovery. We studied the ability of standard echocardiographic parameters to predict left atrial hypertension by reviewing 3 cardiac patients supported with ECMO who subsequently underwent left atrial decompression. We found that standard echocardiographic parameters poorly predict the need for left atrial decompression on ECMO. Following a more specific diagnostic algorithm to estimate left-sided filling pressure in patients with depressed ejection fraction may significantly improve the ability of echocardiography to accurately predict left atrial hypertension and the need for decompression. © The Author(s) 2014.
Keywords: article; case report; child; decompression surgery; decompressive craniectomy; extracorporeal oxygenation; female; heart arrest; heart arrhythmia; heart block; heart catheterization; heart graft; heart muscle biopsy; heart ventricle pressure; heart ventricle tachycardia; human; Human parvovirus B19; human tissue; hypertension; hypoplastic left heart syndrome; left atrial hypertension; lung edema; lung hemorrhage; male; mitral valve regurgitation; mydriasis; myocarditis; polymerase chain reaction; preschool child; priority journal; respiratory failure; retrospective study; school child; septostomy balloon catheter; thorax radiography; transthoracic echocardiography

The pattern of congenital heart disease among neonates referred for echocardiography - Khawahur, H.A.; Sowaiket, H.A.; Saffar, T.A.; Alzaher, G.; Darwich, A.; Qatary, K.A. (Bahrain Medical Bulletin, 2014)
Objective: To define the pattern of congenital heart disease (CHD) among neonates referred for echocardiography. Setting: Department of Pediatrics, Qatif Central Hospital. Design: A Prospective longitudinal and hospital based study. Method: All neonates with suspected CHD referred for echocardiography were reviewed for one year from March 2011. Result: Echocardiography was requested for 289 (9.5%) neonates, male to female ratio 1:1.1, mean birth weight 2.909 kg (range 0.605-5.150 kg); most of them were full-term (86%). One hundred forty-six (50.5%) neonates underwent echocardiography within the first 24 hours (group I). Among those neonates referred for echocardiography, 245 (84.8%) had heart murmur, 9 (3.1%) had cyanosis, 5 (1.7%) had questionable cardiomegaly, 13 (4.5%) had congenital anomalies, and 17 (5.9%) had various anomalies. Heart murmur was detected in 257 (88.9%) during routine neonatal examination. Sixty-four (2.1%) neonates were diagnosed to have CHD, 8 (12.5%) of them have critical congenital heart disease (CCHD). The most common CHD was ventricular septal defect (VSD) 32 (43.2%) followed by secundum atrial septal defect 31 (41.9%). Among 23 neonates with congenital anomalies referred for echocardiography, 10 (43.5%) had Down syndrome. Some neonates had more than one anomaly. Conclusion: Most neonates suspected to have CHD were referred for echocardiography during the first 24 hours. Heart murmur was the most common indication of referral for echocardiography and most of the cases with CHD and CCHD presented with heart murmur alone. Almost all cases of CCHD were diagnosed within the first 72 hours. The most common CHD was VSD followed by secundum ASD. Down syndrome was the most common congenital anomaly referred for echocardiography and 30% of them have CHD.
Keywords: acrocephalosyndactyly; aortic coarctation; article; atrioventricular septal defect; birth weight; cardiomegaly; cleft lip palate; congenital heart disease; cyanosis; Down syndrome; echocardiography; Fallot tetralogy; female; heart atrium septum defect; heart murmur; heart ventricle septum defect; human; hypoplastic left heart syndrome; leprechaunism; longitudinal study; major clinical study; male; meningomyelocele; newborn; newborn care; pediatrics; prematurity; prospective study; prune belly syndrome; pulmonary valve stenosis; skeleton malformation; thorax radiography; tricuspid valve atresia; Philip CX 60; VIVID E7; VIVID E9

Comparing echocardiographic assessment of systolic function with catheterization data in patients with single right ventricles - Husain, N.; Gokhale, J.; Nicholson, L.; Perkins, A.; Cooper, A.L.; Cheatham, J.P.; Holzer, R.J.; Cua, C.L. (Acta Cardiologica, 2014)
Purpose Echocardiographic evaluation of systolic function in patients with single right ventricles (SRV) is important but remains challenging. Minimal data exist correlating echocardiographic indices with catheterization data in this population. The goal of this study was to evaluate which echocardiographic measurement correlated best with dP/dt (max) obtained by cardiac catheterization in SRV patients. Methods Patients with SRV physiology who underwent simultaneous echocardiography and cardiac catheterization were evaluated. Echocardiographic data included fractional area change % (FAC), displacement, TDI s' wave, myocardial performance index (MPI), global systolic strain, and global SR s wave. Maximum positive rate of ventricular pressure change measured as dP/dt (max) was obtained from the cardiac catheterization report. Correlations of echocardiographic and catheterization variables were examined using the Pearson correlation. Results Twenty-seven SRV patients were studied. Median age at the time of the catheterization was 11.4 months (range 0 - 132 months). dP/dt (max) values ranged from 337-1860 mmHg/s with a median of 994 mmHg/s. Mean FAC was 27.15 ± 7.13%, displacement was 7.35 ± 2.88 mm, TDI s' was 4.98 ±1.93 cm/sec, MPI was 0.41 ± 0.17, global strain was -14.85 ± 4.32%, and global SR s wave was -1.03 ± 0.34 sec-1. There were no signifi cant correlations between dP/dt (max) and any of the echocardiographic measurements of systolic function in SRV patients. Conclusion In patients with SRV physiology, catheterization-derived dP/dt (max) did not correlate with echocardiographic measurements of systolic function. Larger studies are needed to determine which non-invasive parameter best describes systolic function in patients with SRV.
Keywords: article; atrioventricular septal defect; cardiovascular parameters; clinical article; cross-sectional study; diastolic blood pressure; displacement behavior; echocardiography; female; fractional area change; Glenn shunt; global systolic strain; heart catheterization; heart disease; heart right ventricle double outlet; heart single right ventricle; heart ventricle pressure; human; hypoplastic left heart syndrome; infant; male; myocardial performance index; post fontan procedure; prospective study; status post hybrid procedure; systolic blood pressure; systolic function; tissue doppler indices; Sensis XP; Vivid

Psychosocial risk in families of infants undergoing surgery for a serious congenital heart disease - Hearps, S.J.; McCarthy, M.C.; Muscara, F.; Hearps, S.J.C.; Burke, K.; Jones, B.; Anderson, V.A. (Cardiology in the Young, 2014)
Objective: The aim of this study was to explore the acute psychosocial risk in families with infants undergoing surgery for a congenital heart disease and, secondarily, to explore the psychosocial impact of antenatal versus post-natal diagnoses. Method: The study sample comprised 39 caregivers (28 mothers) of 29 children diagnosed with a congenital heart disease and requiring surgery within the first 4 weeks of life. Psychosocial risk was measured using the Psychosocial Assessment Tool, which was adapted to include four novel items examining infant risk factors, namely, sleeping, feeding, crying, and bonding difficulties. Parents' psychosocial risk was measured within 4 weeks after their child's surgery and stratified into a three-tiered framework: Universal, Targeted, and Clinical risk. Results: Of the total sample, 61.5% of parents were classified as Universal, that is, at lowest risk; 35.9% as Targeted, and 2.6% as Clinical. The within-family parent total Psychosocial Assessment Tool score correlations were non-significant, and there were no differences between families of infants who received post-natal versus antenatal diagnosis or single ventricle versus biventricular repair. Linear regression found that a higher parent education significantly predicted a lower total Psychosocial Assessment Tool score. Conclusions: Findings indicate that, although the majority of parents adapt to the acute stress of surgery for a serious cardiac illness in their infant, the remaining 38.5% report an increased psychosocial risk associated with higher rates of emotional distress, which may impact on the parental quality of life and capacity for optimal parenting. The distribution of psychosocial risk in parents of children undergoing surgery for a congenital heart disease is consistent with that described for parents of children with other serious paediatric diagnoses. © Cambridge University Press 2013.
Keywords: adult; article; congenital heart disease; correlational study; disease severity; educational status; emotional stress; environmental factor; female; human; male; parental attitude; parental stress; pediatric surgery; perinatal period; prenatal diagnosis; psychologic assessment; psychosocial risk; quality of life; risk; social psychology

Age at referral and mortality from critical congenital heart disease - Fixler, D.E.; Xu, P.; Nembhard, W.N.; Ethen, M.K.; Canfield, M.A. (Pediatrics, 2014)
BACKGROUND AND OBJECTIVE: Newborn pulse oximetry screening is recommended to promote early referral of neonates with critical congenital heart disease (CCHD) and reduce mortality; however, the impact of late referral on mortality is not well defined. The purpose of this population-based study was to describe the association between timing of referral to a cardiac center and mortality in 2360 liveborn neonates with CCHD. METHODS: Neonates with CCHD born before pulse oximetry screening (1996-2007) were selected from the Texas Birth Defects Registry and linked to state birth and death records. Age at referral was ascertained from date of first cardiac procedure at a cardiac center. Logistic and Cox proportional hazards regression models were used to estimate factors associated with late referral and mortality; the Kaplan-Meier method was used to estimate 3-month survival. RESULTS: Median age at referral was 1 day (25th-75th percentile: 0-6 days). Overall, 27.5% (649 of 2360) were referred after age 4 days and 7.5% (178 of 2360) had no record of referral. Neonatal mortality was 18.1% (277 of 1533) for those referred at 0 to 4 days of age, 9.0% (34 of 379) for those referred at 5 to 27 days of age, and 38.8% (69 of 178) for those with no referral. No improvement in age at referral was found across the 2 eras within 1996-2007. CONCLUSIONS: A significant proportion of neonates with CCHD experienced late or no referral to cardiac specialty centers, accounting for a significant number of the deaths. Future population-based studies are needed to determine the benefit of pulse oximetry screening on mortality and morbidity. Copyright © 2014 by the American Academy of Pediatrics.
Keywords: age; article; congenital malformation; cardiovascular mortality; cardiovascular system examination; cause of death; congenital heart disease; controlled study; critically ill patient; cyanosis; early childhood intervention; ethnicity; Fallot tetralogy; female; great vessels transposition; heart failure; high risk infant; human; hypoplastic left heart syndrome; infant; lung vein drainage anomaly; major clinical study; male; newborn; newborn death; newborn intensive care; newborn morbidity; newborn mortality; newborn screening; patient referral; priority journal; pulmonary valve atresia; pulse oximetry; risk reduction; survival time; United States

Novel curved balloon catheter for dilating postoperative angled lesions associated with congenital heart disease - Kise, H.; Miyata, A.; Tomita, H.; Fujii, T.; Fujimoto, K.; Kiguchi, H.; Oyama, N.; Soga, T.; Hata, Y.; Hirata, M.; Itoh, A.; Ishino, K.; et al. (Journal of Interventional Cardiology, 2014)
Objectives This study aimed to analyze the surface stress generated by a novel curved balloon and assess its efficacy for treating angular lesions associated with congenital heart disease. Background Obstructions at the anastomosis of aortopulmonary shunts and cavopulmonary connections may occur postoperatively. Catheter interventions are often performed for such lesions; however, acute angulation may cause balloon slippage or inappropriate stress on the vessel wall. Methods We dilated the curved balloon in a curved vessel model and measured the resultant wall stress and its distribution. Clinical evaluations were performed using this balloon in angled lesions. Results In the curved vessel model, curved balloons generated uniform stress on the lesser and greater curvatures (curved type, lesser/greater=0.343MPa/0.327MPa; P=0.61), whereas straight balloons caused disproportionate stress (straight type, lesser/greater=0.358MPa/0.254MPa; P=0.19). However, the difference in average stress was not statistically significant. Furthermore, the stress was uniform along the entire length of the curved balloon, but differed between the mid and end portions of the straight balloon. Curved balloon dilations were performed for 10 lesions in 7 patients. The curved balloon conformed well to the angulated lesion without slipping. The median percent change in the minimal lumen diameter (MLD) was 64% (range, 0-206%). In 5 lesions, MLD increased by ≥50%. Oxygen saturation increased by 5% (0-9%). Conclusions Although further clinical evaluation is necessary, this novel curved balloon may be a reasonable alternative in angled lesions, providing better conformability and preventing excessive stress to the vessel wall adjacent to the stenosis. (J Interven Cardiol 2014;27:408-413) © 2014, Wiley Periodicals, Inc.
Keywords: Blalock Taussig shunt; aortopulmonary shunt; artery catheter; cavopulmonary connection; systemic pulmonary shunt; elastomer; heparin; polyamide; angiography; aortography; aortopulmonary shunt; artery catheter; artery diameter; artery lesion; article; ascending aorta; balloon dilatation; Blalock Taussig shunt; blood vessel wall; brachiocephalic trunk; cavopulmonary connection; child; clinical article; clinical evaluation; congenital heart disease; coronary artery anomaly; curved balloon catheter; cyanosis; disease association; heart ventricle septum defect; hospital discharge; human; in vitro study; in-stent restenosis; infant; lung hemorrhage; minimal lumen diameter; occlusion balloon catheter; oxygen desaturation; oxygen saturation; phlebography; postoperative angled lesion; postoperative complication; preschool child; priority journal; pulmonary valve atresia; subclavian artery; surface stress; systemic pulmonary shunt; tricuspid valve atresia; vascular guide wire; wall stress; GOKU curve; GOKU straight; Radifocus

Histologic changes in the adrenal gland reflect fetal distress in hydrops fetalis - Taweevisit, M.; Atikankul, T.; Thorner, P.S. (Pediatric and Developmental Pathology, 2014)
The distribution of lipid in the fetal adrenal cortex is reported to correlate with the duration of hypoxia and degree of fetal stress. The original studies were based on Oil Red O staining, requiring frozen tissue that is often not available. To investigate the reliability of these observations, the distribution of lipid in the fetal adrenal cortex was studied in hydrops fetalis (HF) of different etiologies, using immunostaining for adipophilin on formalin-fixed material. Twenty cases of HF due to hemoglobin (Hb) Bart were compared to 34 cases of HF due to other causes. In the fetal zone, lipid distribution was more diffuse in Hb Bart HF compared to other causes of HF, including those due to anemia, supporting the concept that increased lipid in the fetal zone is associated with severity of hypoxia. A more diffuse distribution of lipid correlated with adrenal cytomegaly (P < 0.01) and extramedullary hematopoiesis (P < 0.01) but not Hb level (P = 0.68) nor compact cell change (P = 0.7) or cystic degeneration (P = 0.07) in the definitive zone. A greater degree of cystic degeneration correlated with lower gestational age, rather than the specific etiology of HF. Thus, cystic degeneration is more a reflection of the onset of fetal stress than severity. The combined histologic changes in the fetal and definitive zones of the adrenal gland provide complementary information about fetal status in HF. Immnunostaining for adipophilin circumvents the need for frozen tissue for assessing lipid content by Oil Red O staining, facilitating studies based on archival material. © 2014 Society for Pediatric Pathology.
Keywords: adipophilin; formaldehyde; hemoglobin; hemoglobin H; lipid; adrenal cytomegaly; adrenal disease; adrenal gland; anemia; aortic coarctation; article; congenital heart disease; controlled study; cystic degeneration; cystic lymphangioma; cytomegaly; degeneration; disease severity; Ebstein anomaly; erythropoiesis; extramedullary hematopoiesis; Fallot tetralogy; female; fetus; fetus distress; fetus hydrops; gestational age; histology; human; hypoplastic left heart syndrome; hypoxia; immunohistochemistry; lung hemorrhage; lung malformation; major clinical study; male; myelopoiesis; priority journal; tricuspid valve stenosis; twin twin transfusion syndrome

Use of high-frequency oscillatory ventilation in patients with acute respiratory distress syndrome and cavopulmonary connections: A case report - Sanchez-de-Toledo, J.; Vega, L.; Gil, L.; Balcells, J.; Abella, F.; Gran, F. (Experimental and Clinical Cardiology, 2014)
Mechanical ventilation hampers passive venous flow to the lungs in patients with cavopulmonary connections. When feasible, early extubation may be beneficial in this patient population. In cases of required ventilatory support, understanding of cardiopulmonary interactions is paramount for the election of appropriate ventilatory strategies. Results on the use of high-frequency oscillatory ventilation in these patients remain controversial. We present the case of a child with single ventricle physiology palliated with a cavopulmonary connection who developed acute respiratory distress syndrome in whom the use of high-frequency oscillatory ventilation improved the respiratory and hemodynamic status. The reduced peak inspiratory pressures achieved with high frequency ventilation versus similar parameters of conventional mechanical ventilation may better maintain hemodynamics in patients with parenchymal lung disease and cavopulmonary connections.
Keywords: adult respiratory distress syndrome; article; cardiopulmonary hemodynamics; case report; cavopulmonary connection; child; female; high frequency oscillatory ventilation; high frequency ventilation; human; hypoxemia; oxygenation; positive pressure ventilation; preschool child

Prevalence and profile of congenital heart disease and pulmonary hypertension in Down syndrome in a pediatric cardiology service - Mourato, F.A.; Villachan, L.R.R.; Mattos, S.S. (Revista Paulista de Pediatria, 2014)
Objective: To determine the frequence and profile of congenital heart defects in Down syndrome patients referred to a pediatric cardiologic center, considering the age of referral, gender, type of heart disease diagnosed by transthoracic echocardiography and its association with pulmonary hypertension at the initial diagnosis. Methods: Cross-sectional study with retrospective data collection of 138 patients with Down syndrome from a total of 17,873 records. Descriptive analysis of the data was performed, using Epi-Info version 7. Results: Among the 138 patients with Down syndrome, females prevailed (56.1%) and 112 (81.2%) were diagnosed with congenital heart disease. The most common lesion was ostium secundum atrial septal defect, present in 51.8%, followed by atrioventricular septal defect, in 46.4%. Ventricular septal defects were present in 27.7%, while tetralogy of Fallot represented 6.3% of the cases. Other cardiac malformations corresponded to 12.5%. Pulmonary hypertension was associated with 37.5% of the heart diseases. Only 35.5% of the patients were referred before six months of age. Conclusions: The low percentage of referral until six months of age highlights the need for a better tracking of patients with Down syndrome in the context of congenital heart disease, due to the high frequency and progression of pulmonary hypertension.
Keywords: arteriovenous shunt; article; atriopulmonary connection; atrioventricular septal defect; cardiovascular malformation; congenital heart disease; controlled study; cross-sectional study; descriptive research; disease course; disease severity; Down syndrome; Fallot tetralogy; female; heart atrium septum defect; heart ventricle septum defect; human; incidence; lung artery pressure; major clinical study; male; patent ductus arteriosus; pediatric cardiology; prevalence; pulmonary hypertension; retrospective study; transthoracic echocardiography

Feeding dysfunction in single ventricle patients with feeding disorder - Hill, G.; Silverman, A.; Noel, R.; Bartz, P.J. (Congenital Heart Disease, 2014)
Purpose: To determine whether caregivers of children with single ventricle heart defects identified as having feeding disorder will report more frequent feeding dysfunction, or maladaptive mealtime behavior and/or interactions, when compared with reference populations. Methods: As part of routine evaluation, parents of children evaluated at the Feeding, Swallowing, and Nutrition Center at the Children's Hospital of Wisconsin completed previously validated questionnaires to assess feeding dysfunction and parental stress. Parental responses for single ventricle patients were compared with all other children evaluated with a feeding disorder. Results: Questionnaires were completed in eight patients with single ventricle heart defects. The mean age was 36 ± 23 months, with five females (63%). Mean weight-for-age z-score was -1.4 ± 0.9. Compared with noncardiac feeding clinic children, there was more reported child resistance to eating (83 ± 15% vs. 44 ± 2%; P = .05). Single ventricle parents were more likely to report distress (50 ± 18% vs. 21 ± 2%; P = .04) and a difficult child (63 ± 17% vs. 31 ± 2%; P = .05). There was also more defensive responding among parents of single ventricle children (63 ± 17% vs. 29 ± 2%; P = .04). Conclusion: Single ventricle patients evaluated for disordered feeding more frequently showed resistance to eating and parental distress than noncardiac feeding clinic patients. Parents of these children underestimated the degree of feeding difficulty by defensive responding and had more parental distress. These findings suggest that feeding dysfunction can contribute to longer-term feeding and growth problems in single ventricle patients with feeding disorder. © 2013 Wiley Periodicals, Inc.
Keywords: article; behavior; body weight; caregiver; child; clinical article; controlled study; distress syndrome; eating; feeding; feeding behavior; feeding disorder; female; heart single ventricle; human; male; parent; parental stress; priority journal; questionnaire; social interaction

Substance use, dental hygiene, and physical activity in adult patients with single ventricle physiology - Overgaard, D.; Schrader, A.-M.; Lisby, K.H.; King, C.; Christensen, R.F.; Jensen, H.F.; Moons, P. (Congenital Heart Disease, 2014)
Objectives: The study aims to describe substance use, dental hygiene, and physical activity in adult survivors with single ventricle physiology (SVP) and to compare the behaviors with matched controls, while the patients are particularly at risk for general health problems. Design: The present study is part of a larger research project on long-term outcomes in adult patients with SVP. A cross-sectional, case-control study including 59 patients out of 83 eligible patients participated in the study (response rate 71%). The patients were matched to 172 healthy controls. A questionnaire was mailed to the patients. Nonresponders did not differ significantly from the included participants on age, gender, or physical function. Setting: The study was conducted at the Heart Center of Copenhagen University Hospital or the Department of Cardiology, Aarhus University Hospital. Results: In these patients, 85% report alcohol consumption (92% in controls; odds ratio [OR] = 0.91; P = 0.575); 26% admit "binge drinking" (41% in controls; OR = 0.56; P = 0.041); 20% are cigarette smokers (36% in controls; OR = 0.59; P = 0.100); 12% have used cannabis over the past year (15% in controls; OR = 0.80; P = 0.596); 20% have had no dental visits during the last year (25% in controls; OR = 1.07; P = 0.684); 46% are not flossing their teeth (32% in controls; OR = 1.32; P = 0.239); and 39% are not physically active (24% in controls; OR = 1.63; P = 0.069). Conclusions: While in general there was no significant differences in overall health behaviors between SVP patients and controls, SVP patients are less physically active and are less likely to binge drink. © 2013 Wiley Periodicals, Inc.
Keywords: cannabis; adult; alcohol consumption; article; binge drinking; clinical article; congenital heart malformation; controlled study; female; human; male; mouth hygiene; physical activity; priority journal; questionnaire; single ventricle physiology; smoking; substance use; young adult

Aortic dissection in hospitalized children and young adults: A multiinstitutional study - Shamszad, P.; Barnes, J.N.; Morris, S.A. (Congenital Heart Disease, 2014)
Objective.: To describe the incidence, characteristics, and outcomes of hospitalized children and young adults with aortic dissection (AD). Design.: Retrospective review. Setting.: The Pediatric Health Information System database, a multiinstitutional administrative database. Patients.: All index cases of patients <30 years old hospitalized with AD between January 2004 and June 2011. Outcome Measures.: The primary outcome measure was inpatient mortality. Results.: Of 3800964 hospitalizations, AD was identified in 124 (<1%), accounting for 110 patients (69% male, P = .003) at a median age of 12.9 (interquartile range 3.9-16.8) years with a bimodal distribution in infancy and late adolescence. Associated diagnoses included congenital heart disease (CHD) (38%), trauma (24%), connective tissue disease (CTD) (16%), and isolated hypertension (HTN) (8%). Common CHD diagnoses included aortic arch (24%) and valve (21%) disease, hypoplastic left heart syndrome (10%), and transposition of the great arteries (10%). CHD patients were younger and more likely to undergo inpatient non-AD-related cardiovascular procedures compared with other diagnostic groups (P < .001 for both). Marfan and Ehlers-Danlos syndrome were present in 72% and 11% of CTD patients, respectively. Overall in-hospital mortality in patients with AD was 13% compared with 1% in the database population (odds ratio 12.0, 95% confidence interval 6.9-21.1). By diagnostic category, mortality was 22% in HTN, 22% in CTD, 12% in CHD, and 4% in trauma. Conclusions.: AD is rare in children and young adults but most commonly occurs in CHD and CTD and in males. AD is associated with high inpatient mortality. © 2013 Wiley Periodicals, Inc.
Keywords: adolescence; adolescent; aortic arch anomaly; aortic dissection; aortic valve disease; article; cardiovascular procedure; child; child care; child hospitalization; childhood mortality; congenital heart disease; connective tissue disease; diagnosis related group; Ehlers Danlos syndrome; female; great vessels transposition; hospital patient; human; hypertension; hypoplastic left heart syndrome; incidence; infancy; injury; isolated hypertension; major clinical study; male; Marfan syndrome; medical information system; outcome assessment; preschool child; priority journal; school child

Risk factors in the origin of congenital left-ventricular outflow-tract obstruction defects of the heart: A population-based case-control study - Csáky-Szunyogh, M.; Vereczkey, A.; Kósa, Z.; Gerencsér, B.; Czeizel, A.E. (Pediatric Cardiology, 2014)
The aim of our project was to study possible etiological factors in the origin of congenital heart defects (CHDs) because in the majority of patients the underlying causes are unclear. Cases with different CHD entities as homogeneously as possible were planned for evaluation in the population-based large data set of the Hungarian Case Control Surveillance of Congenital Abnormalities. Dead or surgically corrected 302 live-born cases with different types of left-ventricular outflow tract obstructive defects (LVOT, i.e., valvular aortic stenosis 76, hypoplastic left heart syndrome 76, coarctation of the aorta 113, and other congenital anomalies of aorta 32) were compared with 469 matched controls, 38,151 controls without any defects, and 20,750 malformed controls with other isolated defects. Medically recorded pregnancy complications and chronic diseases were evaluated based on prenatal maternity logbooks, whereas acute diseases, drug treatments, and folic acid/multivitamin supplementation were analyzed both on the basis of retrospective maternal information and medical records. The results of the study showed the role of maternal diabetes in the origin of LVOT in general, while panic disorder was associated with a higher risk of hypoplastic left heart syndrome and ampicillin treatment with a higher risk of coarctation of the aorta (COA). High doses of folic acid had a protective effect regarding the manifestation of LVOT, particularly COA. In conclusion, only a minor portion of causes was shown in our study; thus, further studies are needed to understand better the underlying causal factors in the origin of LVOT. © 2013 Springer Science+Business Media New York.
Keywords: ampicillin; cotrimoxazole; etacrynic acid; folic acid; insulin; magnesium citrate; methyldopa; paracetamol; ritodrine; acute disease; anemia; aortic coarctation; aortic stenosis; subvalvular aortic stenosis; aortic valve stenosis; article; bicuspid aortic valve; cardiovascular risk; child death; chromosome aberration; chronic disease; controlled study; cytomegalovirus infection; disease association; eclampsia; edema; environmental exposure; heart left ventricle outflow tract; heart left ventricle outflow tract obstruction; heart ventricle septum defect; human; hydramnios; hypertrophic cardiomyopathy; hypoplastic left heart syndrome; imminent abortion; insulin dependent diabetes mellitus; kidney disease; major clinical study; maternal age; maternal diabetes mellitus; maternal disease; maternal hypertension; nausea and vomiting; newborn; panic; placenta disorder; population based case control study; preeclampsia; pregnancy complication; pregnancy diabetes mellitus; pregnancy outcome; premature labor; teratogenesis; two dimensional echocardiography; vitamin supplementation

Maternal butalbital use and selected defects in the national birth defects prevention study - Browne, M.L.; Van Zutphen, A.R.; Botto, L.D.; Louik, C.; Richardson, S.; Druschel, C.M. (Headache, 2014)
Background: Butalbital is a barbiturate contained in combination products with caffeine and an analgesic prescribed for the treatment of migraine and tension-type headaches. Controversy exists as to whether butalbital should continue to be prescribed in the United States because of the potential for abuse, overuse headache, and withdrawal syndromes. Butalbital crosses the placenta but there is limited information about potential teratogenicity. Objective: To evaluate associations between butalbital and a wide range of specific birth defects. Methods: The National Birth Defects Prevention Study is an ongoing, case-control study of nonsyndromic, major birth defects conducted in 10 states. The detailed case classification and large number of cases in the National Birth Defects Prevention Study allowed us to examine the association between maternal self-reported butalbital use and specific birth defects. We conducted an analysis of 8373 unaffected controls and 21,090 case infants with estimated dates of delivery between 1997 and 2007; included were birth defects with 250 or more cases. An exploratory analysis examined groups with 100 to 249 cases. Results: Seventy-three case mothers and 15 control mothers reported periconceptional butalbital use. Of 30 specific defect groups evaluated, adjusted odds ratios for maternal periconceptional butalbital use were statistically significant for 3 congenital heart defects: tetralogy of Fallot (adjusted odds ratio = 3.04; 95% confidence interval = 1.07-8.62), pulmonary valve stenosis (adjusted odds ratio = 5.73; 95% confidence interval = 2.25-14.62), and secundum-type atrial septal defect (adjusted odds ratio = 3.06; 95% confidence interval = 1.07-8.79). In the exploratory analysis, an elevated odds ratio was detected for 1 congenital heart defect, single ventricle. Conclusions: We observed relationships between maternal periconceptional butalbital use and certain congenital heart defects. These associations have not been reported before, and some may be spurious. Butalbital use was rare and despite the large size of the National Birth Defects Prevention Study, the number of exposed case and control infants was small. However, if confirmed in additional studies, our findings will be useful in weighing the risks and benefits of butalbital for the treatment of migraine and tension-type headaches. © Published 2013. This article is a U.S. Government work and is in the public domain in the USA.
Keywords: acetylsalicylic acid; butalbital; caffeine; codeine; paracetamol; triptan derivative; adolescent; adult; anus atresia; article; congenital malformation; case control study; child; cleft lip; cleft palate; congenital heart malformation; controlled study; obstetric delivery; disease association; drug use; environmental exposure; exploratory research; female; great vessels transposition; heart atrium septum defect; heart septum defect; heart single ventricle; human; hypoplastic left heart syndrome; hypospadias; major clinical study; male; mother; pregnancy; priority journal; pulmonary valve stenosis; school child; self report; young adult; aspirin

Early postoperative systemic inflammatory response is an important determinant for adverse 2-year neurodevelopment-associated outcomes after the Norwood procedure - Li, X.; Robertson, C.M.T.; Yu, X.; Cheypesh, A.; Dinu, I.A.; Li, J. (Journal of Thoracic and Cardiovascular Surgery, 2014)
Objectives This study investigated the relationship between early postoperative serum C-reactive protein (CRP) levels, a marker of systemic inflammatory response, and 2-year neurodevelopment-associated outcomes among survivors after undergoing the Norwood procedure. Methods Among 53 neonates with hypoplastic left heart syndrome undergoing the Norwood procedure during 2003-2009, CRP was measured in 43 patients twice weekly within postoperative day 20. Two-year cognition, language, and motor scores were assessed with Bayley Scales of Infant and Toddler Development III in 26 patients (9 deaths, 2 lost, and 6 assessed with Bayley Scales of Infant Development II). Peak CRP levels of the 26 patients were recorded, with peak total and differential white blood cell counts (lowest lymphocytes) and glucose. Demographic data included age at surgery, socioeconomic status of the families, durations of cardiopulmonary bypass and aortic crossclamp, deep hypothermic circulatory arrest, and intensive care unit stay. Results The cognitive score was 91 ± 13, language score was 86 ± 13, and motor score was 85 ± 17. The peak CRP level was 79 ± 37 mg/L. Univariate regression showed that the cognitive score significantly and negatively correlated with peak CRP level (P =.004), and trended to a negative correlation with age at surgery (P =.097). The language score significantly and negatively correlated with peak CRP level (P <.0001) and age (P =.005). The motor score trended to a negative correlation with age (P =.08). Multivariate regression showed that both cognitive and language scores significantly and negatively correlated only with peak CRP level (P <.01 for both). Conclusions The magnitude of systemic inflammatory response, among the perioperative factors examined, may be an important determinant for adverse 2-year cognition and language outcomes after the Norwood procedure. Confirmatory studies in larger populations, including those undergoing other types of cardiac surgeries, are warranted. © 2014 by The American Association for Thoracic Surgery.
Keywords: C reactive protein; glucose; article; Bayley Scales of Infant Development; cardiopulmonary bypass; cognition; deep hypothermic circulatory arrest; human; hypoplastic left heart syndrome; intensive care unit; language; length of stay; leukocyte; leukocyte differential count; major clinical study; medical record review; motor performance; nervous system development; newborn; Norwood procedure; operation duration; postoperative inflammation; priority journal; protein blood level; social status; surgical mortality; treatment outcome

Association between Technical Performance Scores and neurodevelopmental outcomes after congenital cardiac surgery - Nathan, M.; Sadhwani, A.; Gauvreau, K.; Agus, M.; Ware, J.; Newburger, J.W.; Pigula, F. (Journal of Thoracic and Cardiovascular Surgery, 2014)
Objectives Technical Performance Score (TPS) has been shown to have a strong association with early and late outcomes after congenital cardiac surgery, with greater morbidity and reintervention in children with major residual lesions (TPS class 3). We sought to explore the effect of TPS on the neurodevelopmental outcomes. Methods All infants undergoing cardiac surgery, excluding those with trisomy 21, were offered neurodevelopmental testing at 1 year of age using the Bayley Scales of Infant Development, 3rd edition. TPSs from the discharge echocardiograms were graded as class 1 (optimal), class 2 (minor residual), or class 3 (major residual). Multivariate regression analysis was performed using patient characteristics and preoperative variables. Results Neurodevelopmental testing was performed in 140 patients at a median age of 16 months. Of these, 28 (20%) had single ventricle palliation; 39 (28%) were in Risk Adjustment for Congenital Heart Surgery category 4 to 6. Significant differences between the groups were found in the cognitive (P =.01) and motor (P =.05) domains, with subjects in TPS class 3 having significantly lower cognitive and motor composite scores. The scores did not vary significantly according to single ventricle versus biventricular repair or Risk Adjustment for Congenital Heart Surgery categorization. In multivariate modeling, class 3 TPS remained significantly associated with a lower Bayley cognitive score (P =.02), with a trend toward a lower Bayley motor score (P =.08). Conclusions We found that TPS is an independent predictor of neurodevelopmental outcomes after infant heart surgery. Future research should explore whether a structured program of intraoperative recognition and intervention on residual lesions can improve the TPS and neurodevelopmental outcomes. © 2014 by The American Association for Thoracic Surgery.
Keywords: article; Bayley Scales of Infant Development; childhood disease; clinical assessment tool; cognition; disease association; disease classification; disease severity; echocardiography; female; heart surgery; human; infant; major clinical study; male; morbidity; motor activity; nerve cell differentiation; palliative therapy; priority journal; retrospective study; technical performance score; trisomy 21

Percutaneous transluminal pulmonary valvuloplasty in a child with tricuspid atresia, ventricular septal defect, and severe pulmonary valve stenosis: Usefulness of the Femoral Artery Approach - Torigoe, T.; Sato, S.; Kanazawa, H. (Catheterization and Cardiovascular Interventions, 2014)
Percutaneous transluminal pulmonary valvuloplasty may be indicated in not only isolated pulmonary valve stenosis, but also complex congenital heart diseases. Because palliative surgery for increasing pulmonary blood flow entails a risk of scar formation and immediate postoperative complications, catheter intervention is preferred, if possible. However, an acute-angled, twisted, or tortuous access route or a small valve orifice occasionally makes it difficult for the catheter to reach or cross the target. We succeeded in performing this intervention for such a complex stenosis effectively and safely in a patient with tricuspid atresia, ventricular septal defect (VSD), and severe pulmonary valve stenosis, thereby evading surgery. In previous reports, the catheter for this cardiac anomaly was accessed via the femoral vein. In the present case, the catheter was advanced through the femoral artery via the aorta, left ventricle, VSD, and right ventricle to the pulmonary valve, using a micro-catheter in a telescopic manner, in combination with a coronary balloon dilatation catheter. This maneuver, which has not been reported previously, made it much easier to perform the procedure as compared to the femoral vein approach, despite the acute turn and the pinhole orifice. Moreover, reported complications of the femoral vein approach, including bradycardia, hypotension, and valve regurgitation, were not observed in this case. We conclude that the femoral artery approach can be a safe and effective alternative in patients for whom a more conventional procedure has been unsuccessful. © 2013 Wiley Periodicals, Inc. Copyright © 2013 Wiley Periodicals, Inc.
Keywords: beraprost; oxygen; article; balloon catheter; Blalock Taussig shunt; case report; child; clinical effectiveness; computer assisted tomography; coronary balloon dilatation catheter; craniofacial synostosis; disease severity; femoral artery; follow up; guide wire; heart right ventricle outflow tract; heart ventricle septum defect; home oxygen therapy; human; male; mental deficiency; microcatheter; oxygen desaturation; oxygen saturation; patient safety; percutaneous transluminal angioplasty balloon; percutaneous transluminal pulmonary valvuloplasty; pulmonary valve atresia; pulmonary valve stenosis; pulmonary valvuloplasty; pulmonary valvuloplasty catheter; school child; sheath removal; surgical approach; systemic pulmonary shunt; tricuspid valve atresia; Carnelian Pixie ER; Maverick XL; Progreat; Ryujin plus OTW; Slalom Thrill; Sprinter Legend RX

Dynamic pulmonary computed tomography angiography: A new standard for evaluation of combined airway and vascular abnormalities in infants - Greenberg, S.B.; Dyamenahalli, U. (International Journal of Cardiovascular Imaging, 2014)
Airway abnormalities are frequently associated with congenital heart disease in infants and children. Respiratory distress in these children frequently requires prolonged respiratory support. Wide-detector dynamic pulmonary computed tomography angiography (DP-CTA) is a non-invasive technique that completely evaluates vascular and airway abnormalities during a single breathe. Our purpose was to evaluate the efficacy of DP-CTA to provide unique actionable information for patient care in newborns and infants with congenital heart disease and persistent respiratory distress. 23 infants with congenital heart disease and persistent respiratory distress underwent DP-CTA. All were intubated at the time of the examinations. The most common cardiac anomalies were tetralogy of Fallot (6) and hypoplastic left heart syndrome variants (5). The most common cardiac surgeries prior to DP-CTA were Norwood (4) and hybrid (3) procedures. The protocol for DP-CTA for intubated infants is four gantry rotations in 1.4 s after intravenous contrast injection. 3D and multiplanar reconstruction with cine loops were created for combined cardiopulmonary imaging. Tracheobronchomalacia was present in 17 children. Lobar bronchomalacia was identified in six children. Branch pulmonary artery stenosis was the most common vascular finding (10 children). Medical management was changed or a surgical procedure performed based on the information resulting from DP-CTA in 16 of the 23 patients (70%). DP-CTA is non-invasive, fast and provides unique information for the management of infants with congenital heart disease and persistent respiratory distress. DP-CTA is uniquely suited for comprehensive and simultaneous evaluation of airway and vascular abnormalities in infants. © Springer Science+Business Media 2013.
Keywords: contrast medium; aortic coarctation; aortic occlusion; article; artificial ventilation; Blalock Taussig shunt; blood pressure; bronchomalacia; chromosome aberration; clinical article; computed tomographic angiography; congenital blood vessel malformation; congenital heart disease; coronary artery obstruction; Down syndrome; dynamic pulmonary computed tomography angiography; Ebstein anomaly; Fallot tetralogy; heart ventricle septum defect; human; hypoplastic left heart syndrome; infant; lung angiography; lung artery banding; lung vein drainage anomaly; non invasive procedure; patent ductus arteriosus; patient care; pulmonary artery stenosis; pulmonary hypertension; pulmonary valve atresia; respiratory distress; respiratory tract disease; right ventricle to pulmonary artery conduit; standard; surgical technique; tracheobronchomalacia; tracheomalacia

Effect of exercise training on sports enjoyment and leisure-time spending in adolescents with complex congenital heart disease: The moderating effect of health behavior and disease Knowledge - Dulfer, K.; Duppen, N.; Blom, N.A.; van Dijk, A.P.J.; Helbing, W.A.; Verhulst, F.C.; Utens, E.M.W.J. (Congenital Heart Disease, 2014)
Objective: The aim of this study was to evaluate the effects of a standardized exercise program on sports enjoyment and leisure-time spending in adolescents with congenital heart disease and to know what the moderating impact of their baseline health behavior and disease knowledge is. Methods: Included were 93 patients, aged 10 to 25, with surgical repair for tetralogy of Fallot or with a Fontan circulation for single-ventricle physiology, of 5 participating centers of pediatric cardiology in NLD. They were randomly allocated, stratified for age, gender, and type of congenital heart disease to a 12-week period with either: (1) three times per week standardized exercise training or (2) care as usual (randomization ratio 2:1). At baseline and after 12 weeks, participants completed Web-based questionnaires and were interviewed by phone. Outcome Measures: Primary analyses tested changes from baseline to follow-up in sports enjoyment and leisure-time spending in the exercise group vs. control group. Secondary analyses concerned the moderating influence of baseline health behavior and disease knowledge on changes from baseline to follow-up, and comparison with normative data. Results: At follow-up, the exercise group reported a decrease in passive leisure-time spending (watching television and computer usage) compared with controls. Exercise training had no effect on sports enjoyment and active leisure-time spending. Disease knowledge had a moderating effect on improvement in sports enjoyment, whereas health behavior did not. Compared with normative data, patients obtained similar leisure time scores and lower frequencies as to drinking alcohol and smoking. Conclusions: Exercise training decreased passive, but not active, leisure-time spending. It did not influence sports enjoyment.
Keywords: adolescent; adult; article; child; computer; congenital heart disease; controlled study; drinking behavior; exercise; Fallot tetralogy; female; Fontan procedure; health behavior; human; knowledge base; leisure; major clinical study; male; Netherlands; priority journal; randomized controlled trial (topic); smoking; sport; television viewing

Impact of chylothorax on the early post operative outcome after pediatric cardiovascular surgery - Ismail, S.R.; Kabbani, M.S.; Najm, H.K.; Shaath, G.A.; Jijeh, A.M.Z.; Hijazi, O.M. (Journal of the Saudi Heart Association, 2014)
Background and aim: Chylothorax is the accumulation of chyle in the pleural cavity, which usually develops after disruption of the thoracic duct along its intra-thoracic route. In the majority of cases, this rupture is secondary to trauma (including cardio thoracic surgeries). Chylothorax is a potentially serious complication after cardiovascular surgeries that require early diagnosis and adequate management. This study aims to determine the risk factors and the impact of chylothorax on the early postoperative course after pediatric cardiac surgery. Methods: A retrospective study of all cases complicated with chylothorax after pediatric cardiac surgery was conducted at King Abdulaziz Cardiac Center between January 2007 and December 2009. Results: There were 1135 cases operated on during the study period. Of these, 57 cases (5%) were complicated by chylothorax in the postoperative period. Thirty patients (54%) were males, while 27 (47%) were females. Ages ranged from 4 to 2759. days. The most common surgeries complicated by chylothorax were the single ventricle repair surgeries (15 cases, 27%); arch repairs (10 cases, 18%); ventricular septal defect repairs (10 cases, 18%); atrioventricular septal defect repairs (7 cases, 12%); arterial switch repair (6 cases, 11%), and others (8 cases, 14%). The intensive care unit (ICU) and the length of hospital stays were significantly longer in the chylothorax group. Additionally, some early postoperative parameters such as incidence of sepsis, ventilation time, and inotropes duration and number were higher in the chylothorax group. Conclusion: Chylothorax after pediatric cardiac surgery is not a rare complication. It occurs more commonly with single ventricle repair and aortic arch repair surgeries, and has a significant impact on the postoperative course and post operative morbidity. © 2014 King Saud University.
Keywords: aortic arch surgery; article; atrioventricular septal defect; cardiovascular risk; cardiovascular surgery; chylothorax; controlled study; female; heart single ventricle; heart ventricle septum defect; hospitalization; human; incidence; infant; intensive care unit; major clinical study; male; pediatrics; postoperative complication; postoperative period; priority journal; retrospective study; sepsis; treatment outcome

Aerobic exercise influences quality of life of children and youngsters with congenital heart disease: A randomized controlled trial - Dulfer, K.; Duppen, N.; Kuipers, I.M.; Schokking, M.; Van Domburg, R.T.; Verhulst, F.C.; Helbing, W.A.; Utens, E.M.W.J. (Journal of Adolescent Health, 2014)
Purpose To evaluate effects of an exercise program on health-related quality of life (HRQoL) in children and adolescents with tetralogy of Fallot (ToF) or a Fontan circulation. Methods Stratified, randomized, controlled intervention study conducted in five participating centers of pediatric cardiology in The Netherlands. In total, 93 patients, aged 10-25 years, with surgical repair for tetralogy of Fallot or with a Fontan circulation for single-ventricle physiology were included. They were randomly allocated with a ratio of 2:1 to: (1) a 12-week period with an exercise program for 3 times per week or (2) to a control group. Randomization was stratified by age, gender, and cardiac diagnosis. At baseline and follow-up after 12 weeks, all participants completed Web-based age-appropriate HRQoL questionnaires. Primary analyses involved change in HRQoL during follow-up. Secondary analyses concerned influence of cardiac diagnosis and comparison with normative data. Results Forty-eight (86%) and 32 (86%) patients in the exercise-group and control-group respectively completed all questionnaires at baseline and follow-up. Compared with the control-group, children, aged 10-15 years, in the exercise-group improved significantly on self-reported cognitive functioning, p <.05, r =.30, and parent-reported social functioning, p <.05, r =.30. Youngsters aged 16-25 years did not change their HRQoL. Cardiac diagnosis had no influence on pre/post changes. Children and youngsters in this study reported comparable or better HRQoL than norm groups. Conclusions Participation in an exercise program improved HRQoL of children with ToF or a Fontan circulation, especially in those with low baseline QoL. © 2014 Society for Adolescent Health and Medicine. All rights reserved.
Keywords: adolescent; adolescent disease; adult; aerobic exercise; article; child; childhood disease; cognition; comparative study; congenital heart disease; controlled study; diagnosis related group; Fallot tetralogy; female; follow up; Fontan circulation; groups by age; Health Related Quality of Life Questionnaire; heart single ventricle; heart surgery; human; intervention study; major clinical study; male; multicenter study; assessment of humans; pediatric cardiology; physical activity; priority journal; quality of life; randomized controlled trial; self report; sex difference; Short Form 36; single blind procedure; social interaction; TNO AZL Child Quality of Life Questionnaire

Early mother-infant relationships after cardiac surgery in infancy - Jordan, B.; Franich-Ray, C.; Albert, N.; Anderson, V.; Northam, E.; Cochrane, A.; Menahem, S. (Archives of Disease in Childhood, 2014)
Objective: The critical importance of a secure mother-infant attachment relationship for long-term physical and mental health of the child is well established. Our study aim was to explore mothers' subjective experience of the mother-infant relationship after discharge from hospital following neonatal cardiac surgery. Design: Participants were 97 infants who underwent cardiac surgery before the age of 3 months and their mothers. Mothers completed Maternal Postnatal Attachment Scale (MPAS) and Edinburgh Postnatal Depression Scale (EPDS) questionnaires and were interviewed after the infant had been discharged home for 4 weeks. Interviews were analysed using inductive thematic analysis. Results: Mean sores on the MPAS were similar to community norms (84.5 (SD 7.2) vs 84.6 (SD 7), p=0.47). 66/91 mothers interviewed described impacts which encompassed four themes; enhanced emotional ties (n=34, 37%), 'bonding' difficulties (n=22, 23%), anxiety and worry (n=17, 19%), and caregiving behaviours (n=10, 11%). Mothers who described bonding difficulties had lower MPAS scores (mean 80.6 (SD 10) vs 85.7 (SD 5.7), p=0.0047), were more likely to have a prenatal diagnosis of the cardiac abnormality (OR 2.6, 95% CI 0.89 to 8.9) and higher EPDS score (9.1 (SD 5.3) vs 6.2 (SD 3.9), p=0.01). Higher EPDS scores were associated with lower MPAS scores (r= -0.44, p=0.0001). Conclusions: Most mothers report a positive relationship with their infant following cardiac surgery but almost a quarter have difficulties forming a strong emotional tie. Clinical care (including prenatal) of the infant with congenital heart disease requiring surgery should include screening, assessment and appropriate referral for early intervention if mothers are struggling to form a bond with their infant.
Keywords: adult; anxiety; aortic arch interruption; aortic coarctation; article; community; Edinburgh Postnatal Depression Scale; Fallot tetralogy; female; great vessels transposition; heart surgery; heart ventricle septum defect; hospital discharge; human; hypoplastic left heart syndrome; infancy; infant; lung vein drainage anomaly; major clinical study; male; maternal postnatal attachment scale; mother; mother child relation; assessment of humans; newborn surgery; Norwood procedure; patent ductus arteriosus; patient worry; personal experience; prenatal diagnosis; priority journal; pulmonary valve atresia; qualitative analysis; telephone interview; thematic analysis; tricuspid valve atresia

Computational fluid dynamics in fontan patients to evaluate power loss during simulated exercise - Bossers, S.S.M.; Cibis, M.; Gijsen, F.J.; Schokking, M.; Strengers, J.L.M.; Verhaart, R.F.; Moelker, A.; Wentzel, J.J.; Helbing, W.A. (Heart, 2014)
Objective Exercise intolerance is common in total cavopulmonary connection (TCPC) patients. It has been suggested that power loss (Ploss) inside the TCPC plays a role in reduced exercise performance. Our objective is to establish the role of Ploss inside the TCPC during increased flow, simulating exercise in a patient-specific way. Methods Cardiac MRI (CMR) was used to obtain flow rates from the caval veins during rest and increased flow, simulating exercise with dobutamine. A 3D reconstruction of the TCPC was created using CMR data. Computational fluid dynamics (CFD) simulations were performed to calculate Ploss inside the TCPC structure for rest and stress conditions. To reflect the flow distribution during exercise, a condition where inferior caval vein (IVC) flow was increased twofold compared with rest was added. 29 TCPC patients (15 intra-atrial lateral tunnel (ILT) and 14 extracardiac conduit (ECC)) were included. Results Mean Ploss at rest was 1.36±0.94 (ILT) and 3.20±1.26 (ECC) mW/m2( p<0.001), 2.84±1.95 (ILT) and 8.41±3.77 (ECC) mW/m2 (p<0.001) during dobutamine and 5.21±3.50 (ILT) and 15.28±8.30 (ECC) mW/m2 (p=0.001) with twofold IVC flow. The correlation between cardiac index and Ploss was exponential (ILT: R2=0.811, p<0.001; ECC: R2=0.690, p<0.001). Conclusions Ploss inside the TCPC structure is limited but increases with simulated exercise. This relates to the anatomy of TCPC and the surgical technique used. In all flow conditions, ILT patients have lower Ploss than ECC patients. We did not find a relationship between Ploss and exercise capacity.
Keywords: dobutamine; article; bicycle ergometry; cardiovascular magnetic resonance; cava vein; cavopulmonary connection; child; clinical article; computational fluid dynamics; cross-sectional study; exercise tolerance; female; flow rate; heart right ventricle double outlet; human; hypoplastic left heart syndrome; male; Netherlands; nuclear magnetic resonance scanner; power loss; priority journal; pulmonary valve atresia; rest; school child; physiological stress; tricuspid valve atresia; General Electric Signa; Philips Achieva; Siemens Avanto

Microscopic chromosome Xp distal deletions - a challenging issue in prenatal genetic counseling - Sukenik-Halevy, R.; Reches, A.; Bar-Shira, A.; Simchoni, S.; Goldstein, M.; Orr-Ortreger, A.; Yaron, Y.; Ben-Shachar, S. (Prenatal Diagnosis, 2014)
Objective: A prenatal diagnosis of chromosome X short arm deletions may present a challenge in prenatal genetic counseling. We present clinical and molecular data of carriers of Xp distal deletions. Methods: We assessed prenatal and postnatal phenotypes of individuals from three families with large Xp distal deletions and from a fourth family with a small Xp distal deletion. The work-up included karyotyping, chromosomal microarray analysis, and assessment of the X inactivation pattern. Results: Five out of eight women with large deletions had a short stature (<3rd percentile). Subjects from one family had developmental and emotional problems. All female carriers with small deletions had markedly short stature, whereas the men had mildly short stature. Chromosomal microarray analysis revealed 11.7-19.3Mb deletions in three families and a small ~1Mb deletion in the fourth. The pseudoautosomal region 1 of the X chromosome was deleted in two families with large deletions. X inactivation was skewed in all tested cases with large deletions. Conclusion: Xp distal deletions are mainly associated with short stature. Skewing of the abnormal X chromosome may attenuate the phenotype in cases with large deletions. We suggest that prenatal evaluation in such cases should include sonographic follow-up and assessment of the X inactivation pattern. © 2014 John Wiley & Sons, Ltd.
Keywords: adult; amniocentesis; article; atrioventricular canal; child; chromosome deletion; chromosome Xp; clinical article; failure to thrive; female; fetus echography; genetic counseling; great vessels transposition; haplotype; heart single ventricle; human; in situ hybridization; karyotyping; microarray analysis; nuchal translucency measurement; phenotype; pregnancy termination; prenatal diagnosis; priority journal; psychomotor disorder; short stature; X chromosome inactivation

Mechanical ventricular assist device as a bridge to recovery post-ABO-incompatible heart transplantation for failed Fontan circulation - Seitz, S.; Buchholz, H.; Rebeyka, I.; Ross, D.; West, L.; Urschel, S. (Transplant International, 2014)
A girl received an ABO-incompatible heart transplantation (ABOiHTx) at the age of 3.5 years for failed univentricular palliation with protein-losing enteropathy (PLE). She was born with a hypoplastic left heart syndrome and underwent multistage palliation to a Fontan circulation at 2 years of age. After the Fontan surgery, she developed PLE, necessitating a Fontan revision, followed by a Fontan takedown and eventually HTx, which was performed with a blood group B heart into an O recipient. Right ventricular (RV) failure secondary to increased pulmonary vascular resistance (PVR) evolved immediately after HTx. A temporary right ventricular assist device (RVAD) was implanted and later switched to a pneumatic pulsatile RVAD. With the adaption of PVR on the RVAD, the PLE resolved and the RVAD was explanted. In the following 12 months, she developed multiple relapses of PLE which eventually resolved after exchange of the calcineurin inhibitor. © 2014 Steunstichting ESOT.
Keywords: albumin; budesonide; cyclosporine; diuretic agent; mycophenolate mofetil; polytetrafluoroethylene; rituximab; sildenafil; spironolactone; steroid; tacrolimus; thymocyte antibody; albumin blood level; article; blood group ABO incompatibility; blood group B; cardiac graft rejection; case report; child; drug substitution; drug withdrawal; female; Fontan procedure; heart catheterization; heart right ventricle failure; heart transplantation; human; hypoplastic left heart syndrome; left ventricular assist device; lung vascular resistance; mitral valve atresia; Norwood procedure; polytetrafluoroethylene implant; preschool child; priority journal; protein losing gastroenteropathy; quality of life; right ventricular assist device; tricuspid valve regurgitation; Centrimag; Excor; Gore-Tex

Compression, distortion and dislodgement of large caliber stents in congenital heart defects caused by cardiopulmonary resuscitation: A case series and review of the literature - Haas, N.A.; Happel, C.M.; Jategaonkar, S.; Moysich, A.; Hanslik, A.; Kececioglu, D.; Sandica, E.; Laser, K.T. (Clinical Research in Cardiology, 2014)
Stenting of vascular, extracardiac or lately intracardiac stenosis has become an established interventional treatment for a variety of problems in congenital or acquired heart disease. Most stent procedures are completed successfully and the long-term outcome is favorable in the majority of cases. Stent collapse or deformation is a well recognized entity in peripheral stents and can be attributed to insufficient radial force; it can also be attributed to excessive external forces, like deformation of stents in the right ventricular outflow tract, where external compression is combined with continuous movement caused by the beating heart. The protection of the thoracic cage may prove to be insufficient in extraordinary circumstances, such as chest compression in trauma or cardiopulmonary resuscitation (CPR). In this case series, we describe three patients in whom large endovascular stents were placed to treat significant stenosis of the aorta, the aortic arch or the venous system of the inferior vena cava close to the atrium. In all patients, CPR was necessary during their clinical course for various reasons; after adequate CPR, including appropriate chest compression all patients survived the initial resuscitation phase. Clinical, echocardiographic as well as radiologic re-evaluation after resuscitation revealed significant stent distortion, compression, displacement or additional vascular injury. The possibility of mechanical deformation of large endovascular stents needs to be considered and recognized when performing CPR; if CPR is successful, immediate re-evaluation of the implanted stents-if possible by biplane fluoroscopy-seems mandatory. © 2014 Springer-Verlag.
Keywords: adult; angiography; aortic stenosis; aortic arch surgery; article; atrioventricular septal defect; balloon dilatation; bare metal stent; case report; cavopulmonary connection; congenital heart malformation; echocardiography; endotracheal tube; female; fluoroscopy; great vessels transposition; heart catheterization; human; hypoplastic left heart syndrome; infant; inferior cava vein; male; medical device complication; arterial switch operation; Norwood procedure; peripheral artery stent; postoperative care; restenosis; resuscitation; stent compression; stent displacement; stent distortion; supraventricular tachycardia; thorax radiography; tracheobronchomalacia; vascular stent; Palmaz Genesis stent; Valeo vascular stent

Chylothorax development in infants and children in the UK - Haines, C.; Walsh, B.; Fletcher, M.; Davis, P.J. (Archives of Disease in Childhood, 2014)
Aim: To describe the incidence, patient profile, management strategies and outcome for infants and children who developed a chylothorax in the UK. Methods: A prospective study of infants and children ≥24 weeks' gestation - ≤16 years, who developed a chylothorax in the UK and were reported through the British Paediatric Surveillance Unit (BPSU). Clinicians completed a questionnaire on the presentation, diagnosis, management and outcome of these children. Three further data sources were accessed to confirm these data. Results: The incidence in children in the UK was 0.0014% (1.4 per 100 000) and 3.2% (3200 per 100 000) for those developing a chylothorax following a cardiac surgical procedure. The incidence was highest in infants ≤12 months at 16 per 100 000 (0.016%). A total of 219 questionnaires were returned with 172 cases meeting the eligibility criteria. Development of a chylothorax was most commonly associated with cardiac surgical procedure (65.1%) and was most frequently confirmed by laboratory verification of triglyceride content of the pleural fluid ≥1.1 mmol/L (66%). Although a variety of management strategies were employed, treatment with an intercostal pleural catheter (86.5%) and a medium chain triglyceride (MCT) diet (89%) was most commonly reported. The majority of the children had a prolonged hospital stay with a reported mortality of 12.2%. Conclusions: Development of a chylothorax in infants and children in the UK was not common. The primary association was with a cardiac surgical procedure. The child's hospital stay was lengthy and therefore the impact on the child, family and hospital resources were significant. Common management strategies existed but national guidance is required to optimise practice. This study allows for better information relating to this serious complication to be given to patients and families and provides the basis for future research and practice development.
Keywords: medium chain triacylglycerol; octreotide; somatostatin; triacylglycerol; adolescent; article; child; chylothorax; Down syndrome; Fallot tetralogy; female; Fontan procedure; heart surgery; human; infant; length of stay; major clinical study; male; morbidity; mortality; newborn; Noonan syndrome; parenteral nutrition; pleurodesis; postoperative complication; priority journal; prospective study; steroid therapy; thoracocentesis; Turner syndrome; United Kingdom

Motor dysfunction and behavioural problems frequently coexist with congenital heart disease in school-age children - Liamlahi, R.; Von Rhein, M.; Bührer, S.; Valsangiacomo Buechel, E.R.; Knirsch, W.; Landolt, M.A.; Latal, B. (Acta Paediatrica, International Journal of Paediatrics, 2014)
Aim Patients with congenital heart disease are at risk of neurodevelopmental deficits. Impairments in motor and behavioural function occur frequently, but no information is available concerning the coexistence of deficits in these two developmental domains. This study explored the occurrence of motor and behavioural deficits and their coexistence in children with surgically corrected congenital heart disease. Methods Outcome was assessed in 95 children with congenital heart disease who had undergone cardiopulmonary bypass surgery. Their mean age was 9.6 years (SD 2.5). Motor function was assessed with the Zurich Neuromotor Assessment and behaviour with the Strength and Difficulties Questionnaire. Results Children with congenital heart disease performed poorer in all motor domains compared with the reference population (all p ≤ 0.001). Behaviour was affected in the domains 'emotional symptoms' and 'hyperactivity/inattention' (both p < 0.01), and 54% of the children with motor abnormalities showed behavioural deficits. Children with coexistent abnormalities in behaviour and motor function had higher rates of remedial school services and therapeutic support. Conclusion Children with congenital heart disease are at risk of long-term motor and behavioural problems, and there is a high rate of coexistence of problems in both domains. Early and longitudinal assessment of all developmental domains is necessary to provide adequate early support. ©2014 Foundation Acta Pædiatrica. Published by John Wiley & Sons Ltd.
Keywords: aortic coarctation; aortic valve stenosis; aortopulmonary septal defect; article; atrioventricular septal defect; attention disturbance; behavior disorder; cardiopulmonary bypass; child; congenital heart disease; controlled study; cor triatriatum; coronary artery fistula; emotional disorder; Fallot tetralogy; female; functional assessment; great vessels transposition; heart atrium septum defect; heart left ventricle double inlet; heart single ventricle; heart ventricle septum defect; human; hyperactivity; inferior cava vein; major clinical study; male; motor dysfunction; motor performance; outcome assessment; priority journal; pulmonary valve atresia; pulmonary valve stenosis; pulmonary vein malformation; questionnaire; risk factor; school child; school health service; Strength and Difficulties Questionnaire; tricuspid valve atresia; Zurich Neuromotor Assessment

Anomalous Left Coronary Artery Connected to the Pulmonary Artery Associated With Other Cardiac Defects: A Difficult Joint Diagnosis - Laux, D.; Bertail, C.; Bajolle, F.; Houyel, L.; Boudjemline, Y.; Bonnet, D. (Pediatric Cardiology, 2014)
Anomalous left coronary artery connected to the pulmonary artery (ALCAPA) can be associated rarely with other congenital heart defects. The preoperative joint diagnosis is challenging. From 1987 to 2012, a retrospective bicentric assessment of 12 patients with ALCAPA related to other cardiac defects focused on the associated heart defect, the moment of complete diagnosis related to surgery, and outcome. Coarctation was the most frequently associated heart defect (n = 5) followed by tetralogy of Fallot with or without pulmonary atresia (n = 3). The study group comprised one case of hypoplastic left heart syndrome, one right aortic arch, one congenital mitral malformation, and one infant with divided left atrium and anomalous pulmonary venous return. Only four patients had a complete diagnosis of both the cardiac defect and the coronary abnormality before surgery. In two cases, the coronary anomaly was discovered during surgery performed for another cardiac defect and treated at the same time. The diagnosis of the six remaining patients was determined after cardiac repair. Of the 12 patients, 7 (58 %) died after surgery. Half of these patients died within the first 30 days after repair. At this writing, the remaining patients are in good health after a median follow-up period of 5.4 years (range, 2.1–8.5 years). This study confirmed that ALCAPA associated with other cardiac defects often is misdiagnosed before surgery, mostly due to specific hemodynamics masking myocardial ischemia preoperatively. Survival was compromised due to the unrecognized diagnosis of an associated coronary abnormality but also because of midterm complications related to the other cardiac defects.
Keywords: aortic arch; aortic coarctation; congenital heart disease; congenital heart malformation; congenital malformation; coronary artery anomaly; diagnosis; Fallot tetralogy; follow up; health; heart; heart left atrium; heart muscle ischemia; hemodynamics; human; hypoplastic left heart syndrome; infant; left coronary artery; lung vein drainage anomaly; patient; pulmonary artery; pulmonary valve atresia; surgery; survival; writing

Factors associated with neurodevelopment for children with single ventricle lesions - Goldberg, C.S.; Lu, M.; Sleeper, L.A.; Mahle, W.T.; Gaynor, J.W.; Williams, I.A.; Mussatto, K.A.; Ohye, R.G.; Graham, E.M.; Frank, D.U.; Jacobs, J.P.; Krawczeski, C.; et al. (Journal of Pediatrics, 2014)
Objective To measure neurodevelopment at 3 years of age in children with single right-ventricle anomalies and to assess its relationship to Norwood shunt type, neurodevelopment at 14 months of age, and patient and medical factors. Study design All subjects in the Single Ventricle Reconstruction Trial who were alive without cardiac transplant were eligible for inclusion. The Ages and Stages Questionnaire (ASQ, n = 203) and other measures of behavior and quality of life were completed at age 3 years. Medical history, including measures of growth, feeding, and complications, was assessed through annual review of the records and phone interviews. The Bayley Scales of Infant Development, Second Edition (BSID-II) scores from age 14 months were also evaluated as predictors. Results Scores on each ASQ domain were significantly lower than normal (P <.001). ASQ domain scores at 3 years of age varied nonlinearly with 14-month BSID-II. More complications, abnormal growth, and evidence of feeding, vision, or hearing problems were independently associated with lower ASQ scores, although models explained <30% of variation. Type of shunt was not associated with any ASQ domain score or with behavior or quality-of-life measures. Conclusion Children with single right-ventricle anomalies have impaired neurodevelopment at 3 years of age. Lower ASQ scores are associated with medical morbidity, and lower BSID-II scores but not with shunt type. Because only a modest percentage of variation in 3-year neurodevelopmental outcome could be predicted from early measures, however, all children with single right-ventricle anomalies should be followed longitudinally to improve recognition of delays. Copyright © 2014 Elsevier Inc. All rights reserved.
Keywords: article; child; child growth; child nutrition; functional status; hearing disorder; heart right ventricle failure; heart transplantation; human; major clinical study; medical history; nerve cell differentiation; nervous system malformation; preschool child; priority journal; quality of life; visual disorder

Health related quality of life after corrective surgery for congenital heart disease - Heusch, A.; Calaminus, G.; Kahl, J.; Schmidt, K. (Klinische Padiatrie, 2014)
After corrective surgery for congenital heart defects (CHD) many patients suffer from residual defects, some with reduced cardiorespiratory capacity and possible impairment of their health related quality of life (HRQoL). The aim of our study is to evaluate, how children after surgery for CHD rate their HRQoL. Method: A standardised questionnaire developed for self-rating in children between 8 and 18 years and dealing with 7 different domains concerning the HRQoL (friends, family, physical functioning, cognition, body image, emotional function and autonomy) was independently answered from patients and their parents during an outpatient visit at their pediatric cardiologist throughout Germany. Results: 173 patients (40% female, 60% male, mean age 11.6 years) were interviewed, 167 questionnaires could be evaluated. The mean time interval after surgery was 9.8±3.4 years. Patient had had surgery for complete different types of CHD (ventricular septal defects n=50, Tetralogy of Fallot n=51, univentricular heart n=26, transposition of great arteries n=40). The results were compared with those of an age-matched control group (n=169). Patients with CHD reported a better HRQoL than the controls for all items (p<0.01). There was no significant gender specific difference. After puberty, the rating for most items, except of body image, had become very similar compared to controls. Parents assessed their children significantly worse in 3 domains (friends, body image and emotion; p<0.01). Conclusion: Children with congenital heart defects are able to develop coping structures, that enable them to live a normal life from their individual point of view. Integration in psychosocial structures seems to be rather normal when compared to healthy controls. Many patients considered their HRQoL as even better. © Georg Thieme Verlag KG Stuttgart New York.
Keywords: adolescent; adult; age distribution; article; body image; child; clinical evaluation; congenital heart disease; controlled study; emotionality; Fallot tetralogy; family interaction; female; human; major clinical study; male; mental capacity; outpatient; patient autonomy; physical capacity; plastic surgery; quality of life; questionnaire; rating scale; school child; sex ratio; treatment duration; young adult

Surgical repair of pulmonary venous stenosis: A word of caution - Kanter, K.R.; Kirshbom, P.M.; Kogon, B.E. (Annals of Thoracic Surgery, 2014)
Background. Pulmonary vein stenosis (PVS), both congenital and acquired, is challenging to treat surgically with uncertain long-term results. We reviewed an 11-year surgical experience in 52 children. Methods. From 2002 to 2012, 52 children age 0 days to 13 years (mean 1.9 years, median 11.7 months) weighing 2.2 to 32.5 kg (mean 9.3 kg, median 7.6 kg) had surgical relief of PVS. Based on clinical characteristics or complexity, 33 (63%) had a sutureless pericardial well repair and 19 (37%) had a more standard patch repair. There were no signi ficant differences in clinical characteristics between the 2 techniques. Twenty children (38%) had prior anomalous pulmonary vein repair and 8 had primary pulmonary vein stenosis; 26 (50%) had other operations at the time of PVS relief. Results. There were 2 hospital deaths (10.5%) in the "standard" group and 5 (15.2%) in the sutureless group (p > 0.99). Despite postoperative evidence of PVS relief by echocardiogram or cardiac cath in all patients, at 5 years, actuarial freedom from PVS recurrence or death in the hospital survivors was 67% in the standard group and 58% in the sutureless group. Most recurrences or deaths occurred within 6 months of operation. Heterotaxy, single ventricle anatomy, bilateral disease, and previous anomalous pulmonary vein repair were not predictors of failure. Conclusions. Surgical treatment of pulmonary vein stenosis remains a challenging problem with nontrivial early mortality and ongoing risk for recurrence or death regardless of surgical technique employed. Clearly, development of methods for earlier intervention or detection and improved surgical techniques are warranted.
Keywords: adolescent; article; cardiopulmonary bypass; catheterization; child; echocardiography; follow up; Fontan procedure; Glenn shunt; heart catheterization; heart single ventricle; heart transplantation; hospital discharge; human; hypoplastic left heart syndrome; infant; infant mortality; lung vein drainage anomaly; major clinical study; newborn; Norwood procedure; patient history of surgery; patient satisfaction; postoperative period; priority journal; pulmonary vein malformation; pulmonary vein obstruction; recurrent disease; reoperation; retrospective study; surgical mortality; survivor

Maternal hypertension with nifedipine treatment associated with a higher risk for right-sided obstructive defects of the heart: A population-based case - Control study - Csáky-Szunyogh, M.; Vereczkey, A.; Gerencsér, B.; Czeizel, A.E. (Heart Asia, 2014)
Objective To establish possible aetiological factors contributing to congenital heart defects (CHD) overall and separately for different types of CHD, as causes are unknown for the vast majority of patients. Design To estimate a possible association with maternal diseases and related drug treatments as exposures in the mothers of cases with right-sided obstructive defects of the heart (RSODH). Setting A large population-based Hungarian Case- Control Surveillance of Congenital Abnormalities data set. Patients Newborn infants with four types of RSODH based on autopsy or surgical records. Interventions Comparison of 200 live-born cases with RSODH including 72 (36.0%) with pulmonary valve stenosis, 13 (6.5%) with tricuspid atresia/stenosis, 7 (3.5%) with Ebstein's anomaly and 108 (54.0%) with pulmonary atresia, with 304 matched controls and 38 151 population controls without any defects. Main outcome measures Risk of any RSODH and risk of each type of RSODH. Results High blood pressure, particularly chronic hypertension with nifedipine treatment, was associated with a risk for RSODH (OR 7.03, 95% CI 3.13 to 13.84). High doses of folic acid reduced the birth prevalence of pulmonary atresia (OR 0.29, 95% CI 0.16 to 0.53). Conclusions The multifactorial threshold model provides the best explanation for the origins of RSODH. Genetic predisposition may be triggered by maternal hypertension with nifedipine treatment, while the risk for pulmonary atresia is reduced by high doses of folic acid in early pregnancy.
Keywords: folic acid; nifedipine; allergic rhinitis; article; autopsy; congenital disorder; congenital heart malformation; constipation; controlled study; diabetes mellitus; drug exposure; drug megadose; dyspepsia; Ebstein anomaly; female; hemorrhoid; human; hypertension; hypotension; live birth; major clinical study; maternal hypertension; migraine; mother; newborn; panic; population based case control study; pulmonary valve atresia; pulmonary valve stenosis; right sided obstructive defects of the heart; risk assessment; skeleton; tricuspid valve atresia; tricuspid valve stenosis; varicosis; cordaflex

Psychosocial risk in families of infants undergoing surgery for a serious congenital heart disease - Hearps, S.J.; McCarthy, M.C.; Muscara, F.; Hearps, S.J.C.; Burke, K.; Jones, B.; Anderson, V.A. (Cardiology in the Young, 2014)
Objective: The aim of this study was to explore the acute psychosocial risk in families with infants undergoing surgery for a congenital heart disease and, secondarily, to explore the psychosocial impact of antenatal versus post-natal diagnoses. Method: The study sample comprised 39 caregivers (28 mothers) of 29 children diagnosed with a congenital heart disease and requiring surgery within the first 4 weeks of life. Psychosocial risk was measured using the Psychosocial Assessment Tool, which was adapted to include four novel items examining infant risk factors, namely, sleeping, feeding, crying, and bonding difficulties. Parents' psychosocial risk was measured within 4 weeks after their child's surgery and stratified into a three-tiered framework: Universal, Targeted, and Clinical risk. Results: Of the total sample, 61.5% of parents were classified as Universal, that is, at lowest risk; 35.9% as Targeted, and 2.6% as Clinical. The within-family parent total Psychosocial Assessment Tool score correlations were non-significant, and there were no differences between families of infants who received post-natal versus antenatal diagnosis or single ventricle versus biventricular repair. Linear regression found that a higher parent education significantly predicted a lower total Psychosocial Assessment Tool score. Conclusions: Findings indicate that, although the majority of parents adapt to the acute stress of surgery for a serious cardiac illness in their infant, the remaining 38.5% report an increased psychosocial risk associated with higher rates of emotional distress, which may impact on the parental quality of life and capacity for optimal parenting. The distribution of psychosocial risk in parents of children undergoing surgery for a congenital heart disease is consistent with that described for parents of children with other serious paediatric diagnoses.
Keywords: adaptive behavior; adult; article; caregiver; child parent relation; congenital heart disease; correlation analysis; crying; disease severity; educational status; emotional stress; family life; female; heart surgery; human; infant feeding; male; mother; normal human; parental behavior; perinatal period; prediction; prenatal diagnosis; psychologic test; Psychosocial Assessment Tool; quality of life; risk assessment; risk factor; sleep; social bonding; social psychology

Feeding dysfunction in children with single ventricle following staged palliation - Hill, G.D.; Silverman, A.H.; Noel, R.J.; Simpson, P.M.; Slicker, J.; Scott, A.E.; Bartz, P.J. (Journal of Pediatrics, 2014)
Objective To determine the prevalence of feeding dysfunction in children with single ventricle defects and identify associated risk factors. Study design Patients aged 2-6 years with single ventricle physiology presenting for routine cardiology follow-up at the Children's Hospital of Wisconsin were prospectively identified. Parents of the patients completed 2 validated instruments for assessment of feeding dysfunction. Chart review was performed to retrospectively obtain demographic and diagnostic data. Results Instruments were completed for 56 patients; median age was 39 months. Overall, 28 (50%) patients had some form of feeding dysfunction. Compared with a normal reference population, patients with single ventricle had statistically significant differences in dysfunctional food manipulation (P <.001), mealtime aggression (P =.002), choking/gagging/vomiting (P <.001), resistance to eating (P <.001), and parental aversion to mealtime (P <.001). Weight and height for age z-scores were significantly lower in subjects with feeding dysfunction (-0.84 vs -0.33; P <.05 and -1.46 vs -0.56; P =.001, respectively). Multivariable analysis identified current gastrostomy tube use (P =.02) and a single parent household (P =.01) as risk factors for feeding dysfunction. Conclusion Feeding dysfunction is common in children with single ventricle defects, occurring in 50% of our cohort. Feeding dysfunction is associated with worse growth measures. Current gastrostomy tube use and a single parent household were identified as independent risk factors for feeding dysfunction.
Keywords: article; body height; body weight; child; childhood disease; clinical article; cohort analysis; comparative study; controlled study; feeding behavior; feeding disorder; female; follow up; gastrointestinal symptom; heart single ventricle; human; hypoplastic left heart syndrome; larynx injury; male; medical record review; palliative therapy; prospective study; retrospective study; stomach tube; vomiting

Long-term results of children operated for hypoplastic left heart syndrome in Children's Heart Centre - Vojtovič, P.; Tláskal, T.; Gebauer, R.; Reich, O.; Chaloupecký, V.; Tomek, V.; Krupičková, S.; Matějka, T.; Hecht, P.; Janoušek, J. (Cor et Vasa, 2014)
Introduction: Hypoplastic left heart syndrome (HLHS), one of the most serious congenital heart defects, can be surgically paliated using 3 subsequent stages. Long-term results of this approach are reviewed in this study. Methods: Fifty-two consecutive patients (pts.) operated for HLHS from 1999 to 2012 were evaluated retrospectively. Results: Norwood stage I operation was performed at the median age of 6.5 days with a total mortality of 19%. Significant risk factor for death was lower weight at surgery (Cox proportional risk per 1 g increase = 0.997, CI 0.995-0.990, P < 0.001). Between stages I and II, 15 catheter/surgical reintervention had to be carried out in 13 pts. (aortic arch narrowing in 10/13). Forty-two pts. underwent stage II operation at the median age of 6.8 months with a total mortality of 4.8% and 18 subsequent reinterventions in 13 patients. Finally, 26 patients aged median 3.9 years underwent stage III operation (total cavopulmonary connection) with a total mortality of 8%. The probability of survival at 1/5/10 years of age was 77/77/71%. At long-term follow up (median 7.8 years) 37 of the 38 surviving patients are in NYHA functional class I or II. Conclusions: Despite a highly centralized care, surgical treatment of HLHS is still associated with a significant mortality and morbidity. Long-term survivals, however, have an accept- able functional status during childhood corresponding to other groups of patients after surgical palliation for functionally single ventricle.
Keywords: antiarrhythmic agent; anticonvulsive agent; inotropic agent; adolescent; adrenal cortex insufficiency; annuloplasty ring; anticonvulsant therapy; aortopulmonary shunt; article; autism; Blalock Taussig shunt; body weight; cardiac resynchronization therapy; cause of death; cavopulmonary connection; child; chylothorax; complete heart block; controlled study; Damus Kaye Stansel procedure; dyslexia; enteropathy; female; fenestration; follow up; functional status; heart failure; heart left ventricle failure; heart muscle ischemia; heart right bundle branch block; heart surgery; hospitalization; human; hypoplastic left heart syndrome; junctional ectopic tachycardia; long term care; long term survival; major clinical study; male; mediastinitis; metabolic disorder; morbidity; New York Heart Association class; Norwood procedure; cardiac rhythm management device; pacemaker implantation; palliative therapy; pediatric surgery; percutaneous transluminal angioplasty; postoperative complication; pulmonary artery stenosis; reoperation; retrospective study; right ventricle to pulmonary artery conduit; risk factor; second degree atrioventricular block; sepsis; special education; staged palliation; staging; surgical mortality; surgical risk; survival time; tricuspid annuloplasty; tricuspid valve regurgitation; tricuspid valve repair; tricuspid valve replacement

Foetal therapy, what works? An overview - Mellander, M.; Gardiner, H. (Cardiology in the Young, 2014)
The update course in foetal cardiology held by the Fetal Working Group of the Association for European Paediatric and Congenital Cardiology in Istanbul in May 2012 included a session on foetal cardiac therapy. In the introductory overview to this symposium, we critically examine the level of evidence supporting or refuting proposed foetal cardiac therapies including transplacental treatment of foetal tachyarrhythmias, steroid treatment in foetal atrioventricular block, and foetal aortic valvuloplasty. In summary, the evidence for the ef ficiency and safety of currently available foetal cardiac therapies is low, with no therapy based on a randomised controlled trial. Transplacental treatment of foetal tachycardia is generally accepted as effective and safe, based on extensive and widespread clinical experience; however, there is no consensus on which drugs are the most effective in different electrophysiological situations. Randomised studies may be able to resolve this, but this is complicated because tachyarrhythmias are relatively rare conditions, the foetus is not accessible for direct treatment, and it is the healthy mother who accepts treatment she does not need on behalf of her foetus. The indications for steroid treatment in foetal atrioventricular block and for foetal valvuloplasty are even more controversial. Although randomised trials would be desirable, the practical issues of recruiting sufficient sample sizes and controlling for variation in practice across multiple sites is not to be underestimated. Multicentre registries, analysed free of bias, may be an alternative way to improve the evidence base of foetal cardiac therapy.
Keywords: antiarrhythmic agent; digoxin; flecainide; fluorinated steroid; placebo; sotalol; steroid; aortic valve stenosis; article; atrioventricular block; cardiomyopathy; drug efficacy; drug response; electrophysiology; fetal aortic valve stenosis; fetal atrioventricular block; fetal atrioventricular block; fetal balloon valvuloplasty; fetal heart block; fetal heart block; fetal tachycardia; fetal tachycardia; fetal therapy; fetus disease; heart block; hepatitis; human; hypoplastic left heart syndrome; myocarditis; outcome assessment; prenatal care; prognosis; pulmonary atresia intact ventricular septum; pulmonary valve stenosis; quality of life; safety; sinus rhythm; tachycardia; treatment indication; valvuloplasty

Endoscopic removal of subgaleal hematoma in a 7-year-old patient treated with anticoagulant and antiplatelet agents - Hayashi, Y.; Kita, D.; Furuta, T.; Oishi, M.; Hamada, J.-I. (Surgical Neurology International, 2014)
Background: Subgaleal hematomas frequently occur in children after head trauma and extend over the cranial sutures. Although conservative treatment suffices in most cases, surgical removal of a subgaleal hematoma is indicated when the patient presents with anemia and headache associated with its progressive enlargement. Copyright: Case Description: We present the case of a 7-year-old boy who was medicated with warfarin and aspirin due to a hypoplastic left ventricle and fell from a rock wherein he hit his head in the frontal region. Although a computed tomography scan of the head revealed no intracranial lesion, an extracranial hematoma was found to extend over the cranial sutures, leading to the diagnosis of subgaleal hematoma. The hematoma continued to grow gradually despite the cessation of warfarin and aspirin therapy immediately after the head trauma. Since the patient's headache and anemia were progressing as the hematoma enlarged, removal of the hematoma was performed 3 days after admission. Endoscopic hematoma removal was planned to enable accurate coagulation of the sites of bleeding and removal of the maximal amount of hematoma through minimal incision. The hematoma was completely removed, and the patient's postoperative course was excellent with alleviation of both the anemia and the headache. No sign of hematoma recurrence could be detected during 2 years follow-up. Conclusion: An angled endoscope can allow visualization of the deep subgaleal space, and this technique enabled direct visualization of the bleeding sites and accurate coagulation to prevent recurrence of hematoma. Endoscopic techniques, such as minimally invasive techniques, can allow sufficient removal of subgaleal hematoma with minimal morbidity, especially in patients such as ours.
Keywords: acetylsalicylic acid; warfarin; article; brain hematoma; brain surgery; case report; child; clinical feature; computer assisted tomography; consciousness disorder; conservative treatment; cranial suture; disease course; head injury; headache; human; hypoplastic left heart syndrome; male; postoperative period; priority journal; school child; stupor; subgaleal hematoma; treatment response

Bosentan improves exercise capacity in adolescents and adults after fontan operation: The TEMPO (treatment with endothelin receptor antagonist in fontan patients, a randomized, placebo-controlled, double-blind study measuring peak oxygen consumption) study - Hebert, A.; Mikkelsen, U.R.; Thilen, U.; Idorn, L.; Jensen, A.S.; Nagy, E.; Hanseus, K.; Sørensen, K.E.; Søndergaard, L. (Circulation, 2014)
Background-The Fontan procedure has improved survival in children with functionally univentricular hearts. With time, however, complications such as reduced exercise capacity are seen more frequently. Exercise intolerance is multifactorial, but pulmonary vascular resistance probably plays a crucial role. Elevated pulmonary vascular resistance has been associated with raised levels of endothelin-1, which are common both before and after Fontan operations. Treatment with endothelin-1 receptor antagonists could theoretically improve cardiopulmonary hemodynamics and exercise capacity. The aim of this study was therefore to examine the efficacy and safety of bosentan in Fontan patients. Methods and Results-Seventy-five adolescents and adults were randomized 1:1 to 14 weeks of treatment with bosentan or placebo. Cardiopulmonary exercise test, functional class, blood samples, and quality-of-life questionnaires were evaluated at baseline and at the end of treatment. Sixty-nine patients (92%) completed the study. Peak oxygen consumption increased 2.0 mL·kg-1·min-1 (from 28.7 to 30.7 mL·kg-1·min-1) in the bosentan group compared with 0.6 mL·kg-1·min-1 (from 28.4 to 29.0 mL·kg-1·min-1) in the placebo group (P=0.02). Cardiopulmonary exercise test time increased by 0.48 minute (from 6.79 to 7.27 minutes) versus 0.08 minute (from 6.94 to 7.02 minutes; P=0.04). Nine bosentan-treated patients improved 1 functional class, whereas none improved in the placebo group (P=0.0085). Side effects were mild and occurred equally in both groups. No serious adverse effects were seen, and no patients had liver enzyme levels above the 3-fold upper limit. Conclusions-Bosentan improves exercise capacity, exercise time, and functional class in Fontan patients without serious adverse events or hepatotoxicity.
Keywords: NCT01292551; aminotransferase; bosentan; brain natriuretic peptide; oxygen; placebo; adult; aminotransferase blood level; anaerobic threshold; arthralgia; article; backache; cardiopulmonary exercise test; controlled study; depressed blood pressure; double blind procedure; drug effect; drug efficacy; drug safety; drug withdrawal; dyspepsia; edema; exercise tolerance; faintness; fatigue; female; flushing; Fontan procedure; functional assessment; heart muscle oxygen consumption; heart palpitation; human; major clinical study; male; nausea; New York Heart Association class; outcome assessment; protein blood level; protein losing gastroenteropathy; pruritus; quality of life; randomized controlled trial; recurrent disease; Short Form 36; side effect; systolic blood pressure; thorax pain

Chromosome 22q11.21 microduplication in association with hypoplastic left heart syndrome with hypoplastic pulmonary arteries - McMahon, C.J.; Morgan, C.T.; Greally, M.T. (Cardiology in the Young, 2014)
We describe a case of a baby girl born with hypoplastic left heart syndrome consisting of mitral atresia, aortic atresia, hypoplastic ascending aorta, and left ventricle. The pulmonary arteries were hypoplastic, measuring 3 mm. Fluorescence in situ hybridisation analysis demonstrated a microduplication of chromosome 22q11.2. Subsequent array comparative genomic hybridisation showed a gain of 2.3 Mb in one copy of chromosome 22q at band 22q11.21. The proband underwent a successful Norwood procedure with Sano shunt and subsequently underwent bi-directional Glenn shunt and Fontan procedure. This report highlights the association between hypoplastic left heart syndrome with hypoplastic pulmonary arteries and chromosome 22q11.21 microduplication.
Keywords: anamnesis; aorta anomaly; aortic atresia; artery diameter; article; ascending aorta; ascending aorta hypoplasia; case report; cesarean section; chromosome 22q; chromosome duplication; chromosome microduplication 22q21; comparative genomic hybridization; cyanosis; disease association; ECG abnormality; face dysmorphia; female; fetus echography; fluorescence in situ hybridization; Fontan procedure; gestational age; Glenn shunt; heart atrium septum defect; heart catheterization; heart left right shunt; heart left ventricle; heart murmur; heart right ventricle hypertrophy; human; human tissue; hypoplastic left heart syndrome; hypoplastic pulmonary artery; infant; mitral valve atresia; Norwood procedure; oxygen saturation; pulmonary artery malformation; right ventricle to pulmonary artery conduit; speech delay; surgical approach; surgical technique

Early pregnancy exposure to antihistamines and risk of congenital heart defects: results of two case–control studies - Smedts, H.P.M.; de Jonge, L.; Bandola, S.J.G.; Baardman, M.E.; Bakker, M.K.; Stricker, B.H.C.; Steegers-Theunissen, R.P.M. (European Journal of Epidemiology, 2014)
We aimed to study the association between use of antihistamines in early pregnancy and congenital heart defects (CHD) in the offspring. Design: Two case–control studies. Setting: HAVEN study, Erasmus MC, University Medical Centre, Rotterdam, and Eurocat Northern Netherlands (NNL), University Medical Center Groningen, Groningen, the Netherlands. We studied 361 children with CHD and 410 controls without congenital malformations from the HAVEN study and replicated the analyses in 445 children with CHD and 530 controls from the Eurocat NNL registry. Information about antihistamine use in early pregnancy and potential confounders was obtained from questionnaires postpartum. We calculated the association between antihistamines and CHD risk by multivariable logistic regression analysis. Main outcome measures: Odds ratios (OR) with 95 % confidence intervals (CI). In the HAVEN study, 25 of 771 mothers used antihistamines that were associated with an increased CHD risk (OR 3.0, 95 % CI 1.2–7.3), particularly atrioventricular septal defects (AVSD) (OR 5.1, 95 % CI 1.3–20.5) and perimembranous ventricular septal defects (pVSD) (OR 5.1, 95 % CI 1.8–14.4). Mothers with severe nausea who did not use antihistamines had a reduced risk (OR 0.7, 95 % CI 0.5–0.98), whereas nauseous mothers using antihistamines showed an almost fivefold increased risk of pVSD (OR 4.8, 95 % CI 1.1–21.8). The association between antihistamines and AVSD was confirmed in the Eurocat cohort (OR 3.5, 95 % CI 1.4–8.7), but we could not replicate the association with overall CHD risk. We found a positive association between antihistamine use in early pregnancy and CHD risk, particularly AVSD, which seemed to be independent of nausea/vomiting.
Keywords: antihistaminic agent; cetirizine; levocetirizine; meclozine; meclozine plus pyridoxine; adult; age distribution; aortic valve stenosis; article; atrioventricular septal defect; case control study; congenital heart malformation; controlled study; disease association; disease severity; Fallot tetralogy; female; first trimester pregnancy; heart single ventricle; heart ventricle septum defect; heredity; human; hypoplastic left heart syndrome; major clinical study; male; maternal age; mitral valve atresia; nausea; nausea and vomiting; outcome assessment; perimembranous ventricular septal defect; phenotype; prenatal drug exposure; pulmonary valve stenosis; risk factor; risk reduction; tricuspid valve atresia

Congenital heart disease in infancy and childhood - Bellsham-Revell, H.; Burch, M. (Medicine (United Kingdom), 2014)
Congenital heart disease occurs in approximately 8/1000 live births. The most common lesion at birth is a ventricular septal defect but many are small and do not need surgery. Cyanotic heart disease includes Fallot's tetralogy and transposition of the great arteries, which are both amenable to correction in childhood. More complicated cyanotic lesions are treated by separation of the systemic venous flow by a cavopulmonary connection, often referred to as a Fontan circulation. Some genetic syndromes are associated with congenital heart disease (Marfan's, Noonan's, Williams'), as are chromosomal disorders such as Down's and Turner's. DiGeorge's syndrome (thymic aplasia, hypoparathyroidism and cono-truncal cardiac defect) and velocardiofacial syndrome (palatal abnormalities, heart defects and dysmorphic features) are associated with microdeletions within the q11 region of chromosome 22.
Keywords: aortic coarctation; aortic stenosis; article; congenital heart disease; Down syndrome; Eisenmenger complex; Fallot tetralogy; gene deletion; genetic disorder; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; Holt Oram syndrome; human; lung vein drainage anomaly; Marfan syndrome; Noonan syndrome; patent ductus arteriosus; pregnancy termination; prenatal diagnosis; priority journal; pulmonary valve stenosis; spontaneous abortion; stillbirth; Turner syndrome

Congenital heart disease in adults - Fitzsimmons, S.; Salmon, A. (Medicine (United Kingdom), 2014)
Major advances in paediatric cardiac surgery over recent years have resulted in an increased number of children with congenital heart disease (CHD) surviving into adulthood. Currently in Europe, the adult CHD population is greater than that of the paediatric CHD population. This changing prevalence and ageing congenital population brings with it multiple comorbidities and new challenges in all areas of their medical, surgical and psychological management. This article gives an introduction to the common conditions presenting acutely to general physicians, long-term complications, treatment options and the long-term considerations for end-of-life care. Adult congenital heart disease patients are safest treated in a network with a multidisciplinary team approach.
Keywords: amiodarone; anticoagulant agent; beta adrenergic receptor blocking agent; dipeptidyl carboxypeptidase inhibitor; diuretic agent; acute heart failure; adult; adulthood; anticoagulant therapy; aortic coarctation; article; atriopulmonary connection; cardioversion; congenital heart disease; diuretic therapy; Eisenmenger complex; emergency care; Fallot tetralogy; Fontan procedure; general practitioner; great vessels transposition; heart atrium arrhythmia; heart atrium septum defect; heart palpitation; heart surgery; heart ventricle arrhythmia; heart ventricle septum defect; holistic care; human; long term care; lung blood flow; palliative therapy; prevalence; priority journal; quality of life; randomized controlled trial (topic); terminal care

Using bayesian models to assess the effects of under-reporting of cannabis use on the association with birth defects, national birth defects prevention study, 1997-2005 - Van Gelder, M.M.H.J.; Donders, A.R.T.; Devine, O.; Roeleveld, N.; Reefhuis, J. (Paediatric and Perinatal Epidemiology, 2014)
Background: Studies on associations between periconceptional cannabis exposure and birth defects have mainly relied on self-reported exposure. Therefore, the results may be biased due to under-reporting of the exposure. The aim of this study was to quantify the potential effects of this form of exposure misclassification. Methods: Using multivariable logistic regression, we re-analysed associations between periconceptional cannabis use and 20 specific birth defects using data from the National Birth Defects Prevention Study from 1997-2005 for 13 859 case infants and 6556 control infants. For seven birth defects, we implemented four Bayesian models based on various assumptions concerning the sensitivity of self-reported cannabis use to estimate odds ratios (ORs), adjusted for confounding and under-reporting of the exposure. We used information on sensitivity of selfreported cannabis use from the literature for prior assumptions. Results: The results unadjusted for under-reporting of the exposure showed an association between cannabis use and anencephaly (posterior OR 1.9 [95% credible interval (CRI) 1.1, 3.2]) which persisted after adjustment for potential exposure misclassification. Initially, no statistically significant associations were observed between cannabis use and the other birth defect categories studied. Although adjustment for under-reporting did not notably change these effect estimates, cannabis use was associated with esophageal atresia (posterior OR 1.7 [95% CRI 1.0, 2.9]), diaphragmatic hernia (posterior OR 1.8 [95% CRI 1.1, 3.0]), and gastroschisis (posterior OR 1.7 [95% CRI 1.2, 2.3]) after correction for exposure misclassification. Conclusions: Under-reporting of the exposure may have obscured some cannabis-birth defect associations in previous studies. However, the resulting bias is likely to be limited.
Keywords: cannabis; adult; anencephalus; anus atresia; aortic coarctation; article; Bayes theorem; congenital malformation; cannabis use; cleft lip palate; cleft palate; controlled study; craniofacial synostosis; diaphragm hernia; disease association; esophagus atresia; Fallot tetralogy; female; gastroschisis; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; human; hypoplastic left heart syndrome; hypospadias; limb defect; major clinical study; microtia; newborn; population based case control study; pregnancy; pulmonary valve stenosis; quantitative study; self report; sensitivity and specificity; spinal dysraphism

Late consequences of the fontan operation - Rychik, J.; Goldberg, D.J. (Circulation, 2014)
Keywords: acetylsalicylic acid; alanine aminotransferase; albumin; alpha 1 antitrypsin; aspartate aminotransferase; budesonide; plasma protein; sildenafil; abdominal radiography; abdominal swelling; adolescent; alanine aminotransferase blood level; albumin blood level; article; ascites; aspartate aminotransferase blood level; body height; body weight; cardiovascular magnetic resonance; case report; central venous pressure; chronic vein insufficiency; drug withdrawal; echocardiography; exercise; feces analysis; Fontan procedure; forward heart failure; fulminant hepatic failure; gastrointestinal biopsy; gastrointestinal endoscopy; Glenn shunt; heart catheterization; heart output; heart right ventricle pressure; human; hypoplastic left heart syndrome; ileum; inflammation; liver biopsy; liver fibrosis; low drug dose; lung artery pressure; lung vascular resistance; lymphangiectasis; male; physical activity; priority journal; protein blood level; protein losing gastroenteropathy; quality of life; platelet count; thromboembolism; tricuspid valve regurgitation; venous return

Outcomes of straightforward extracardiac Fontan operation in advanced-age group - Prachasilchai, P.; Promphan, W.; Katanyuwong, P.; Layangool, T.; Sangtawesin, C.; Kirawittaya, T.; Mokarapong, P. (Journal of the Medical Association of Thailand, 2014)
Introduction: Fontan operation is a palliative procedure used in patients with univentricular heart (UVH). There have been numerous modifications to the technique. The appropriate strategy for treating patients with UVH in Thailand is still a major concern. Objective: To describe the outcomes of patients after straightforward Fontan operation at advanced-age and evaluate their post-surgical cardiac performance. Material and Method: A cross sectional study was performed in post-Fontan operation patients at Rajvithi Hospital between 2000 and 2009. Post-operative cardiac performance was analyzed using the echocardiogram and treadmill exercise stress test (EST). Results: Thirty-nine patients were enrolled in the present study. The mean age was 11.7 years and the mean age at operation was 7.4 years. The predominant systemic chamber was morphologic left ventricle. Straightforward Fontan operation was performed in 60% of cases. Mean of Fontan index, mean of McGoon ratio, and mean of Nakata index were 2.63, 2.32, and 414.15 sqmm/sqm, respectively. Mean of the PVR and PAP were 1.98 U/m2 and 11.05 mmHg. Eighteen percent of patients died in the early post-operative period. Most of the patients died from septicemia. The mean EF was 58.43 %. Systolic dysfunction in 17.9% of the cases was abnormal, whereas diastolic dysfunction was present in half of the cases. Thirty-nine percent had MPI abnormality. During EST, three cases developed arrhythmias and 3 cases had hypotension. Patients were categorized into 3 groups (Group 1: normal systolic and diastolic functions, Group 2: diastolic dysfunction, Group 3: impairment of both systole and diastole). Pre-operative cardiac catheterization parameters, surgical data and cardiac performance showed no statistical significance. However, there was a significant correlation between those with abnormal cardiac performance and arrhythmias or hypotension during EST (p = 0.003). Conclusion: The selection of suitable cases and good pre-operative evaluation could decrease the morbidity and mortality in patients undergoing the Fontan procedure. This study also found a correlation between abnormal cardiac performance and transient cardiac arrhythmia during exercise. The evaluation of cardiac performance and EST remains to be performed for following-up of patients who have undergone the Fontan operation, even for the asymptomatic cases.
Keywords: acid phosphatase prostate isoenzyme; article; cavopulmonary connection; child; clinical article; cross-sectional study; diastolic dysfunction; echocardiography; female; Fontan procedure; heart arrhythmia; heart ejection fraction; heart palpitation; heart performance; heart single ventricle; human; hypotension; male; myocardial perfusion imaging; outcome assessment; postvoid residual urine volume; septicemia; systolic dysfunction; tissue Doppler imaging; treadmill exercise

Extreme winter temperature and birth defects: A population-based case-control study - Van Zutphen, A.R.; Hsu, W.-H.; Lin, S. (Environmental Research, 2014)
Background/objective: We examined the relationship between extreme winter temperatures and birth defects to determine whether pregnant women might be vulnerable to the weather extremes expected with climate change. Methods: In this population-based, case-control study, we linked the New York State Congenital Malformations Registry to birth certificates (1992-2006). Cases were defined as live births with birth defects, and controls were selected from a 10% random sample of live births. We assigned meteorological data based on maternal birth residence and summarized universal apparent temperature across gestational weeks 3-8 (embryogenesis). We defined an extreme cold day as a day with mean temperature below the 10th percentile of the regional winter temperature distribution and a cold spell as 3 consecutive extreme cold days. We averaged temperature for each week of the first trimester to identify susceptible periods. We estimated adjusted odds ratios (ORs) and 95% confidence intervals (CIs) with multivariable logistic regression for 30 birth defects groups. Results: Among 13,044 cases and 59,884 controls with at least 1 week of embryogenesis in winter, coarctation of the aorta was associated with a 1. °C decrease in mean universal apparent temperature (OR 1.06, 95% CI 1.02-1.11), cold spell (OR 1.61, 95% CI 1.11-2.34), and number of extreme cold days. We observed reduced odds of hypoplastic left heart syndrome and dislocated hip for some cold indicators. Conclusions: Most birth defects were not associated with cold indicators; however, we found positive associations between cold indicators and coarctation of the aorta in the biologically-relevant developmental window which warrants replication.
Keywords: ozone; adult; aortic coarctation; aortic valve stenosis; article; choana atresia; cleft lip; cleft palate; climate change; cold; congenital cataract; congenital hip dislocation; congenital malformation; controlled study; diaphragm hernia; embryo development; endocardial cushion defect; Fallot tetralogy; female; first trimester pregnancy; gastroschisis; gestational age; heart atrium septum defect; heart ventricle septum defect; hip dislocation; Hirschsprung disease; human; hydrocephalus; hypoplastic left heart syndrome; hypospadias; intestine atresia; kidney agenesis; low birth weight; major clinical study; maternal age; maternal smoking; microcephaly; omphalocele; patent ductus arteriosus; population based case control study; pregnant woman; premature labor; priority journal; pulmonary valve atresia; pylorus stenosis; smoking; spinal dysraphism; tracheoesophageal fistula; vapor pressure; winter; young adult

A common angiotensin-converting enzyme polymorphism and preoperative angiotensin-converting enzyme inhibition modify risk of tachyarrhythmias after congenital heart surgery - Smith, A.H.; Flack, E.C.; Borgman, K.Y.; Owen, J.P.; Fish, F.A.; Bichell, D.P.; Kannankeril, P.J. (Heart Rhythm, 2014)
Background The angiotensin-converting enzyme insertion/deletion (ACE I/D) polymorphism is described in association with numerous phenotypes, including arrhythmias, and may provide predictive value among pediatric patients undergoing congenital heart surgery. Objective The purpose of this study was to examine the role of a common polymorphism on postoperative tachyarrhythmias in a large cohort of pediatric patients undergoing congenital heart surgery with cardiopulmonary bypass (CPB). Methods Subjects undergoing congenital heart surgery with CPB at our institution were consecutively enrolled from September 2007 to December 2012. In addition to DNA, perioperative clinical data were obtained from subjects. Results Postoperative tachyarrhythmias were documented in 45% of 886 enrollees and were associated with prolonged mechanical ventilation (P <.001) and intensive care unit length of stay (P <.001). ACE I/D was in Hardy-Weinberg equilibrium (19% I/I, 49% I/D, 32% D/D). I/D or D/D genotypes were independently associated with a 60% increase in odds of new tachyarrhythmia (odds ratio [OR] 1.6, 95% confidence interval [CI] 1.1-2.3, P =.02). Preoperative ACE inhibitor administration was independently associated with a 47% reduction in odds of postoperative tachyarrhythmia in the entire cohort (OR 0.53, 95% CI 0.32-0.88, P =.01), driven by a 5-fold reduction in tachyarrhythmias among I/I genotype patients (OR 0.19, 95% CI 0.04-0.88, P =.02). Conclusion The risk of tachyarrhythmias after congenital heart surgery is independently affected by the ACE I/D polymorphism. Preoperative ACE inhibition is associated with a lower risk of postoperative tachyarrhythmias, an antiarrhythmic effect that appears genotype dependent. An understanding of genotype variation may play an important role in the perioperative management of congenital heart surgery.
Keywords: beta adrenergic receptor blocking agent; digoxin; dipeptidyl carboxypeptidase; dipeptidyl carboxypeptidase inhibitor; DNA; age; article; artificial ventilation; atrioventricular junction arrhythmia; body weight; cardiopulmonary bypass; cardiovascular risk; child; cohort analysis; comparative study; controlled study; disease association; disease course; endocardial cushion defect; enzyme inhibition; enzyme polymorphism; Fallot tetralogy; female; gene deletion; genotype; heart atrium septum defect; heart surgery; heart ventricle septum defect; heart ventricle tachycardia; human; hypoplastic left heart syndrome; incidence; infant; intensive care; length of stay; major clinical study; male; medical history; newborn; Norwood procedure; perioperative period; pharmacogenetics; postoperative complication; postoperative period; preoperative period; priority journal; prophylaxis; risk reduction; scoring system; supraventricular tachycardia; tachycardia

A near lethal case of plastic bronchitis following truncal valve replacement - Lang, K.; Champion, E.; Cosper, G.; Peeler, B.; Maxey, T. (Journal of Pediatric Intensive Care, 2013)
Plastic bronchitis is a condition in which large, rubber-like, bronchial casts develop in the tracheobronchial tree causing airway obstruction. It is an unusual disorder that occurs in various disease states. Most case reports of plastic bronchitis associated with congenital heart disease are in patients palliated with Fontan physiology. We describe a 13-year-old girl with DiGeorge syndrome and truncus arteriosus who underwent an uneventful truncal valve replacement. The child developed plastic bronchitis on postoperative day eight requiring extra-corporeal membrane oxygenation support and daily bronchoscopy to remove bronchial casts. Our patient did not have elevated systemic venous pressures or Fontan physiology. We speculate the etiology of plastic bronchitis may have been surgical trauma to the lymphatic channels surrounding the bronchi and disruption of pleural adhesions. A comprehensive evaluation revealed no specific cause and the diagnosis of idiopathic plastic bronchitis was made. © 2013 - IOS Press and the authors. All rights reserved.
Keywords: heparin; warfarin; adolescent; anticoagulation; arterial trunk; article; bronchitis; bronchoscopy; case report; DiGeorge syndrome; extracorporeal oxygenation; female; follow up; human; lethality; nasal cannula; priority journal; right ventricle to pulmonary artery conduit; treatment outcome; truncus vagotomy

Outcome of univentricular repair in patients with Down syndrome - Furukawa, T.; Park, I.-S.; Yoshikawa, T.; Nishimura, T.; Takahashic, Y.; Ando, M.; Wada, N. (Journal of Thoracic and Cardiovascular Surgery, 2013)
Objective: Total cavopulmonary connection (TCPC) is rarely performed for a functional single ventricle in children with Down syndrome; therefore, the postsurgical outcomes are not well known. We evaluated mortality and related factors after TCPC in children with Down syndrome. Methods: Between January 2004 and March 2010 we identified 8 patients with Down syndrome among 235 patients who had undergone TCPC. The preoperative clinical course, preoperative data, and postoperative clinical course were evaluated. In addition, clinical parameters and postoperative clinical course were compared between children with Down syndrome (n = 8) and a non-Down syndrome group (n = 227). Results: The median age at the time of TCPC was 4.1 years (range, 3.4-5.5 years), and the preoperative mean pulmonary artery pressure was 13.9 ± 1.81 mm Hg. We observed respiratory complications in 2 patients, surgical site infection in 3 patients, and chylothorax in 2 patients. No significant difference was observed in preoperative data and mortality rate (1 of 8 patients [12.5%] in the Down syndrome group; 5 of 227 patients [2.2%] in the non-Down syndrome group) between the groups of children with and without Down syndrome. However, when the postoperative clinical course was examined, the durations of intensive care unit stay (P =.009) and hospital stay (P =.007) were found to be significantly prolonged in the Down syndrome group. Conclusions: Patients with Down syndrome tend to show prolonged recovery after TCPC. However, as opposed to previous reports, the mortality rate of patients undergoing TCPC is lower with no significant difference from that of children without Down syndrome. Copyright © 2013 by The American Association for Thoracic Surgery.
Keywords: article; artificial ventilation; cavopulmonary connection; child; chylothorax; clinical article; disease course; Down syndrome; female; follow up; heterotaxy syndrome; hospitalization; human; hypoplastic left heart syndrome; intensive care unit; lung artery pressure; male; mortality; oxygen saturation; preoperative care; preschool child; priority journal; protein losing gastroenteropathy; pulmonary hypertension; pulmonary vascular disease; retrospective study; sudden death; surgical infection; total cavopulmonary connection

Psychosocial experiences of parents of infants with hypoplastic left heart syndrome in the PICU - Cantwell-Bartl, A.M.; Tibballs, J. (Pediatric Critical Care Medicine, 2013)
Objective: To evaluate the psychosocial status of mothers and fathers of infants with hypoplastic left heart syndrome while in the PICU. Design: A retrospective study combining interviews and psychometric testing of parents. Setting: Tertiary hospital PICU. Subjects: Twenty-nine parents (16 mothers and 13 fathers) of surviving children. Intervention: A semistructured face-to-face interview was conducted to explore parental experiences, and a Structured Clinical Interview for Diagnosis-Clinical Version (posttraumatic stress disorder module) was conducted to determine the possibility of an acute stress disorder or a posttraumatic stress disorder. Measurement and Main Results: All parents reported multiple stresses which commenced with their infant's diagnosis and endured throughout their infant's time in PICU. The Structured Clinical Interview for Diagnosis revealed that acute stress disorder or posttraumatic stress disorder developed in 24 parents (83%). Of 18 parents whose infants were diagnosed with hypoplastic left heart syndrome in utero, eight of nine mothers (88%) and six of nine fathers (66%) had posttraumatic stress disorder. Of 11 parents whose infants were diagnosed with hypoplastic left heart syndrome postbirth, six of seven mothers had acute stress disorder and one mother had posttraumatic stress disorder, and of four fathers, two fathers had acute stress disorder and one father had posttraumatic stress disorder. The prevalence of parental stress-related disorder was not different between mothers and fathers (p = 0.85). Only five parents were free of traumatic stress-related illness. Parents also experienced losses. Many parents were marginalized from their infant's care by the environment of PICU. Fifty percent of mothers experienced difficulties with parental-infant bonding. Ten parents (34%) began the process of adaptation to their infant's hypoplastic left heart syndrome and were assisted by the support and sensitivity of staff or had discovered other resources. Conclusions: All parents of surviving infants with hypoplastic left heart syndrome in PICU, irrespective of timing of diagnosis, experienced numerous stresses and losses, and the majority exhibited clinical levels of traumatic stress. Receiving the diagnosis itself is very traumatic and is compounded by the environment of the PICU which alienates parents from their infants and interferes with parent-infant bonding. Parental adaptation to this situation can be assisted by staff. Copyright © 2013 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: acute stress disorder; adaptation; adolescent; adult; article; child; child care; child death; child parent relation; clinical article; doctor patient relationship; family life; father; female; human; hypoplastic left heart syndrome; intensive care unit; male; mother; narrative; parental stress; posttraumatic stress disorder; prenatal diagnosis; preschool child; priority journal; prognosis; psychometry; religion; retrospective study; school child; semi structured interview; social psychology; Structured Clinical Interview for DSM Disorders; support group; young adult

Upper body central venous catheters in pediatric cardiac surgery - Miller, J.W.; Vu, D.N.; Chai, P.J.; Kreutzer, J.H.; John, J.B.; Vener, D.F.; Jacobs, J.P. (Paediatric Anaesthesia, 2013)
Summary Background A central venous catheter located in the jugular or subclavian vein provides rapid, reliable vascular access for pediatric heart surgery. However, intravascular catheters are associated with vessel injury. Stenosis or thrombosis of central veins in the upper body can lead to 'superior vena cava syndrome' with markedly elevated venous pressures in the head and neck, causing facial swelling and headaches. This complication may be especially serious for patients with superior cavopulmonary (Glenn) or total cavopulmonary (Fontan) circulation. The authors hypothesized that upper body central line placement would be associated with a low risk of venous thrombosis or stenosis. Methods A three-year retrospective review of infant and univentricular cardiac procedures at a single institution was performed. Two hundred and thirty-five consecutive cardiac surgical patients <1 year of age or undergoing palliation for univentricular cardiac anatomy up to five years of age during January 2010 to December 2012 were included in this study. Upper body central lines are routinely placed by the anesthesiologist after induction of anesthesia for pediatric cardiac surgery at the study institution. The major exception is existing central venous access via an umbilical vein or femoral vein. Patients <2 years of age received a 4.0-French, 5-cm double-lumen central line [Cook Medical polyurethane, no antibiotic or heparin coating]. Those over two years of age received a 5.0-French, 8-cm triple lumen central line [Cook Medical polyurethane, no antibiotic or heparin coating]. A retrospective review of charts, hospital reports, echocardiographic studies, and cardiac catheterization studies was performed. Results The combined population of infants <1 year of age and patients <5 years of age with functional univentricular hearts totaled 235 patients who underwent 261 cardiac surgical operations. In this cohort of 261 cases, 171 size 4.0 or 5.0-French upper body central lines were inserted. A total of 158 right internal jugular vein catheters were placed. Two left internal jugular lines, two left subclavian lines, and nine right subclavian lines were placed in this population after failure to obtain right internal jugular access. Due to the small sample size (N = 13), the central lines not placed in the right internal jugular vein were excluded from further review. Two cases with right internal jugular venous lines were excluded due to death (without known stenosis or thrombosis) with the line in place. Twenty-three size 4.0- or 5.0-French right internal jugular central venous lines were placed in patients over one year of age (range 1.1-4.3 years) having modified Glenn- or Fontan-type surgery. The central lines were removed with a median of 1.4 days after insertion (range 0.7-8.2 days) for these older children, compared with a median of 4.2 days of age (range 0.3-19.3 days) for the 133 children <1 year of age. Retrospective chart review of nursing notes, progress notes, cardiology notes, discharge summaries, echocardiographic reports, and cardiac catheterization reports for all patients who received an upper body central venous line (internal jugular or subclavian) showed no definitive diagnosis of an upper body venous stenosis or thrombosis related to the central venous line. A further targeted review of echocardiographic and cardiac catheterization studies for univentricular cardiac patients failed to show stenosis or thrombosis of a vessel associated with upper body central line placement. Conclusions This study describes one institution's experience with routine upper body central venous catheter placement for neonatal and infant cardiac surgery as well as univentricular cardiac palliation (Glenn and Fontan procedures) with minimal risk of clinically significant catheter-associated vessel thrombosis or stenosis. No upper body central venous stenosis or thrombosis was detected in association with perioperative catheter placement in the upper body central venous system, primarily the right internal jugular vein in 156 cases. Right internal jugular central line placement for infant cardiac surgery can be utilized with a low risk of direct venous thrombosis or stenosis. © 2013 John Wiley & Sons Ltd.
Keywords: polyurethan; anesthesia induction; article; brachiocephalic vein; cardiac patient; central venous catheter; child; chylothorax; Fallot tetralogy; femoral vein; Fontan procedure; Glenn shunt; heart catheterization; heart single ventricle; heart surgery; human; hypoplastic left heart syndrome; infant; inferior cava vein; internal jugular vein; major clinical study; Norwood procedure; palliative therapy; pediatric surgery; peripherally inserted central venous catheter; preschool child; priority journal; retrospective study; risk reduction; stenosis; subclavian vein; surgical patient; umbilical vein; vein thrombosis

Higher-hazard, no benefit research involving children: Parental perspectives - Sachdeva, T.; Morris, M.C. (Pediatrics, 2013)
OBJECTIVES: US regulations allow local institutional review boards to approve greater than minimal risk, no-benefit research when the research enrolls children with the condition under study but not when it enrolls healthy children. We aim to describe the opinions of parents regarding higher-hazard, no-benefit research METHODS: Quantitative and qualitative interviews with parents of children without heart disease or chronic medical conditions (no heart disease [noHD], n = 30), children with fully correctable heart disease (FCHD, n = 30), and children with life-altering heart disease (LAHD, n = 30). RESULTS: Parents of children with heart disease endorse higherhazard, no-benefit heart disease research more strongly than noHD parents. Eight of 30 noHD parents, 19 of 30 FCHD parents, and 26 of 30 LAHD parents reported willingness to enroll their children in a heart disease research study involving an otherwise unnecessary chest radiograph (P , .01). There was no difference among groups in willingness to enroll their children in a similar study focused on childhood cancer. Twenty-two of 30 FCHD and 30 of 30 LAHD parents reported that parents have a responsibility to enroll their children in medical research to help future children with heart disease. Twentyone of 30 noHD parents, 29 of 30 FCHD parents, and 30 of 30 LAHD parents feel able to evaluate the risks of medical research (P = .01). CONCLUSIONS: Parental opinions regarding higher-hazard, no-benefit research align with federal regulations. Parental willingness to enroll their children in higher-hazard, no-benefit research is driven in part by a sense of obligation to a community of families affected by childhood heart disease. Pediatrics 2013;132:e1302-e1309. Copyright © 2013 by the American Academy of Pediatrics.
Keywords: aortic coarctation; aortic disease; appendicitis; article; bronchiolitis; cardiomyopathy; cellulitis; child; childhood cancer; controlled study; Fallot tetralogy; female; fever; funnel chest; great vessels transposition; heart arrhythmia; heart atrium septum defect; heart single ventricle; heart ventricle septum defect; higher hazard no benefit research; human; hypertension; infant; injury; interview; male; medical research; mitral valve stenosis; parental attitude; parental behavior; pneumonia; preschool child; priority journal; public opinion; pulmonary hypertension; pyelonephritis; qualitative research; quantitative study; school child; thorax radiography; tonsillectomy

Maternal race/ethnicity and survival experience of children with congenital heart disease - Wang, Y.; Liu, G.; Druschel, C.M.; Kirby, R.S. (Journal of Pediatrics, 2013)
Objective To investigate the existence of racial/ethnic disparity in mortality risk among children with individual congenital heart defects and identify any other risk factors. Study design The study cohort, comprising children born between 1983 and 2006 with a selected congenital heart defect, was matched to death records to ascertain vital status. The birth and maternal risk factors were obtained from birth certificates. Results After adjusting for covariates using a multivariate regression model, the risk of mortality was significantly higher in children of non-Hispanic black mothers with transposition of the great arteries (hazard ratio (HR), 1.31; 95% CI, 1.07-1.60), tetralogy of Fallot (HR, 1.34; 95% CI, 1.06-1.69), and coarctation of the aorta (HR, 1.40; 95% CI, 1.10-1.79), compared with children of non-Hispanic white mothers. Time trends analysis examining the mortality risk by survival age and birth period found a significant decrease in 5-year mortality risk from 1983 to 2003 births, with a nearly 50% reduction for hypoplastic left heart syndrome and coarctation of the aorta across 3 maternal racial/ethnic groups examined. Conclusion Our findings may help identify at-risk populations and mortality risk factors and thereby contribute to improved survival and quality of life for these children across the lifespan. © 2013 Mosby Inc. All rights reserved.
Keywords: aortic coarctation; article; congenital heart disease; ethnic difference; ethnicity; Fallot tetralogy; female; great vessels transposition; human; hypoplastic left heart syndrome; infant; major clinical study; male; maternal age; mortality; overall survival; phenotype; priority journal; race difference; risk factor; sex difference; survival rate

Quality of life and cognitive function in Fontan patients, a population-based study - Idorn, L.; Jensen, A.S.; Juul, K.; Overgaard, D.; Nielsen, N.P.; Sørensen, K.; Reimers, J.I.; Søndergaard, L. (International Journal of Cardiology, 2013)
Background After the Fontan procedure patients are at risk for reduced quality of life (QoL) and cognitive function. We aimed to assess these important factors in Danish Fontan patients and to compare the results with a group of healthy controls. Methods All Fontan patients living in Denmark were identified and invited to participate. QoL was evaluated using the Pediatric Quality of Life Inventory (PedsQL) version 4.0 generic core module in patients < 16 years and the Short Form 36 questionnaire (SF-36) in patients ≥ 16 years. Cognitive function was evaluated in all patients ≥ 6 years using the Quick Test of Cognitive Speed. To evaluate if QoL correlated with exercise capacity, patients performed a symptom-limited bicycle test. Results 158 of 179 eligible patients (88%) consented to participate. Median age was 13.9 years (IQR: 10.2-19.3). PedsQL scores increased with age but were significantly lower among patients than among controls. SF-36 physical scores were significantly lower in patients compared to controls while psychosocial scores were similar. Cognitive speed was significantly reduced in patients at all ages compared to controls. No significant difference in PedsQL-/SF-36 scores or cognitive speed was found between hypoplastic left heart syndrome (HLHS) and non-HLHS Fontan patient. PedsQL-/SF-36 scores in patients ≥ 10 years correlated significantly to cognitive speed but not to peak exercise capacity. Conclusion QoL is reduced in Fontan children compared to their healthy counterparts whereas in patients ≥ 16 years only physical, but not psychosocial QoL is reduced. Cognitive speed was significantly lower in patients at all ages compared to controls. © 2013 Elsevier Ireland Ltd.
Keywords: adolescent; article; child; child behavior; cognition; controlled study; Denmark; emotion; female; Fontan procedure; functional assessment; human; hypoplastic left heart syndrome; major clinical study; male; mental function; mental health; physical capacity; priority journal; quality of life; questionnaire; rating scale; school child; scoring system; Short Form 36; social interaction

Effect of inhaled iloprost on the exercise function of Fontan patients: A demonstration of concept - Rhodes, J.; Ubeda-Tikkanen, A.; Clair, M.; Fernandes, S.M.; Graham, D.A.; Milliren, C.E.; Daly, K.P.; Mullen, M.P.; Landzberg, M.J. (International Journal of Cardiology, 2013)
Background Exercise capacity following Fontan surgery is often depressed. An inability to reduce pulmonary vascular resistance appropriately during exercise may contribute to this phenomenon. The aim of this study was to determine whether administration of iloprost, a selective pulmonary vasodilator, would improve exercise function after Fontan procedure. Methods Double-blind, randomized, placebo controlled, crossover trial. Patients performed two cardiopulmonary exercise tests (CPX) separated by < 1 month. A single nebulizer treatment (iloprost or placebo) was administered before each CPX. Results 18 patients aged 12-49 (median 17) years were recruited. Mild throat discomfort developed in 10/18 patients during iloprost administration; all but 1 were able to complete treatment. No symptoms developed during placebo treatments (p < 0.001). Two additional patients did not complete CPX: one with atrial flutter; another with developmental issues that precluded adequate CPX. In the 15 remaining subjects oxygen pulse (a surrogate for forward stroke volume) at peak exercise was higher following iloprost (median increase 1.2 ml/beat; p < 0.001). Peak VO2 also rose (median increase 1.3 ml/kg/min; p < 0.04). Nine patients had peak VO2 < 30 ml/kg/min; each of these patients had higher peak VO2 following iloprost. Only 3/6 patients with peak VO2 > 30 ml/kg/min had higher peak VO2 following iloprost (p < 0.04). Conclusions Iloprost improves the peak oxygen pulse and peak VO2 of patients with Fontan physiology and appears to be particularly beneficial among patients with impaired exercise function. Treatment is associated with minor side effects. These findings support the concept of pulmonary vasodilator therapy in Fontan patients with limited functional capacity. © 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: iloprost; oxygen; placebo; adolescent; adult; article; cardiopulmonary exercise test; child; clinical article; controlled study; crossover procedure; double blind procedure; drug effect; exercise; female; Fontan procedure; heart atrium flutter; heart single ventricle; human; hypoplastic left heart syndrome; male; nebulizer; oxygen tension; postoperative period; priority journal; prospective study; randomized controlled trial; school child; sore throat; thorax pain; tricuspid valve atresia

Neurodevelopmental outcomes for children with hypoplastic left heart syndrome at the age of 5 years - Brosig, C.; Mussatto, K.; Hoffman, G.; Hoffmann, R.G.; Dasgupta, M.; Tweddell, J.; Ghanayem, N. (Pediatric Cardiology, 2013)
This study aimed to determine the neurodevelopmental (ND) outcome for children with hypoplastic left heart syndrome (HLHS) at early school age. English-speaking patients who underwent the Norwood procedure between 2000 and 2005 were eligible at 4-6 years of age for ND testing. Of the 72 eligible patients, 44 (61 %) agreed to participate, and 37 completed ND testing before the close of the study. Three subjects were excluded from analyses due to late stroke. The ND testing included intelligence, visual motor integration, memory and motor and language skills. Parents and teachers completed measures of behavior and attention problems. Subjects' scores and parent/teacher ratings were converted to z-scores and compared with test norms. Higher scores on child measures represent better outcomes, whereas higher scores on parent and teacher rating scales indicate more problems. The average ND performance of the tested cohort fell within one standard deviation of the test norms for all measures. However, the subjects performed significantly lower than the test norms on measures of visual-motor integration, fine motor skills, memory, and word structure (z = -0.42 to -0.54; p < 0.005). On the parent and teacher completed measures, the subjects scored higher than the test norms on attention problems (z = 0.40-0.62; p < 0.005). Although the overall ND performance of the cohort was normal, the subjects showed relative weakness in visual motor and attention skills. Ongoing developmental monitoring of these children is recommended to guide interventions that may improve individual outcomes and to assess the impact of changes in clinical management strategies on functional outcomes. © 2013 Springer Science+Business Media New York.
Keywords: article; attention; child; child behavior; Child Behavior Checklist; female; hand movement; human; hypoplastic left heart syndrome; integration; intelligence; language; major clinical study; male; memory; motor performance; nerve cell differentiation; Norwood procedure; occupational therapy; pediatric surgery; physiotherapy; preschool child; speech therapy; Wechsler intelligence scale

22q11.2 deletions in patients with conotruncal defects: Data from 1,610 consecutive cases - Peyvandi, S.; Lupo, P.J.; Garbarini, J.; Woyciechowski, S.; Edman, S.; Emanuel, B.S.; Mitchell, L.E.; Goldmuntz, E. (Pediatric Cardiology, 2013)
The 22q11.2 deletion syndrome is characterized by multiple congenital anomalies including conotruncal cardiac defects. Identifying the patient with a 22q11.2 deletion (22q11del) can be challenging because many extracardiac features become apparent later in life. We sought to better define the cardiac phenotype associated with a 22q11del to help direct genetic testing. 1,610 patients with conotruncal defects were sequentially tested for a 22q11del. The counts and frequencies of primary lesions and cardiac features were tabulated for those with and those without a 22q11del. Logistic regression models investigated cardiac features that predicted deletion status in tetralogy of Fallot (TOF). Deletion frequency varied by primary anatomic phenotype. Regardless of the cardiac diagnosis, a concurrent aortic arch anomaly (AAA) was strongly associated with deletion status [odds ratio (OR), 5.07; 95 % confidence interval (CI), 3.66-7.04]. In the TOF subset, the strongest predictor of deletion status was an AAA (OR, 3.14; 95 % CI 1.87-5.27; p < 0.001), followed by pulmonary valve atresia (OR, 2.03; 95 % CI 1.02-4.02; p = 0.04). Among those with double-outlet right ventricle and transposition of the great arteries, only those with an AAA had a 22q11del. However, 5 % of the patients with an isolated conoventricular ventricular septal defect and normal aortic arch anatomy had a 22q11del, whereas no one with an interrupted aortic arch type A had a 22q11del. A subset of patients with conotruncal defects are at risk for a 22q11del. A concurrent AAA increases the risk regardless of the intracardiac anatomy. These findings help to direct genetic screening for the 22q11.2 deletion syndrome in the cardiac patient. © 2013 Springer Science+Business Media New York.
Keywords: 22q11.2 deletion syndrome; aortic arch anomaly; arterial trunk; article; child; chromosome 22q; clinical feature; congenital heart disease; conotruncal cardiac defect; Fallot tetralogy; female; fluorescence in situ hybridization; gene deletion; genetic association; genetic screening; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; human; infant; learning disorder; major clinical study; male; multiplex ligation dependent probe amplification; palatopharyngeal incompetence; phenotype; predictive value; preschool child; pulmonary valve atresia; pulmonary valve stenosis; school child

Prevalence and trends of selected congenital malformations in New York state, 1983 to 2007 - Kim, K.; Wang, Y.; Kirby, R.S.; Druschel, C.M. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2013)
BACKGROUND: Major birth defects result in high infant mortality and morbidity. It is important to evaluate the burden of birth defects and trends for future intervention and public health improvement. Using the New York State (NYS) Congenital Malformations Registry data, we examined the prevalence and trends of birth defects among children in NYS during 25 years of surveillance. METHODS: Children who had any of the 21 selected birth defects and were born to NYS residents between 1983 and 2007 were selected. The prevalence of each defect was characterized by demographic and birth factors, and the prevalence ratio was calculated. Live births of NYS residents for the same birth year period were used as the denominators for calculating the prevalence. The prevalence trends of birth defects were analyzed by maternal age and race/ethnicity. RESULTS: Compared with non-Hispanic whites, we detected 33%, 21%, and 37% higher prevalence of encephalocele, lower limb deficiencies and omphalocele among non-Hispanic blacks, respectively, and 22% higher prevalence of gastroschisis among Hispanics. Increasing trends of gastroschisis and Down syndrome among non-Hispanic blacks and decreasing trends of spina bifida and limb deficiencies were observed in NYS. CONCLUSION: The findings from this study suggest the existence of racial disparities among children with selected birth defects in NYS. The increasing trends of gastroschisis and Down syndrome observed in NYS are consistent with nationwide trends. © 2013 Wiley Periodicals, Inc.
Keywords: anencephalus; anophthalmia; article; atrioventricular septal defect; cleft face; cohort analysis; congenital malformation; diaphragm hernia; disease surveillance; Down syndrome; encephalocele; esophagus atresia; ethnicity; Fallot tetralogy; follow up; gastroschisis; great vessels transposition; human; hypoplastic left heart syndrome; intestine atresia; limb defect; live birth; major clinical study; maternal age; microphthalmia; omphalocele; prevalence; priority journal; race difference; spinal dysraphism; United States

Pharmacological and non-pharmacological therapy for arrhythmias in the pediatric population: EHRA and AEPC-Arrhythmia Working Group joint consensus statement - Brugada, J.; Blom, N.; Sarquella-Brugada, G.; Blomstrom-Lundqvist, C.; Deanfield, J.; Janousek, J.; Abrams, D.; Bauersfeld, U.; Brugada, R.; Drago, F.; De Groot, N.; Happonen, J.-M.; et al. (Europace, 2013)
In children with structurally normal hearts, the mechanisms of arrhythmias are usually the same as in the adult patient. Some arrhythmias are particularly associated with young age and very rarely seen in adult patients. Arrhythmias in structural heart disease may be associated either with the underlying abnormality or result from surgical intervention. Chronic haemodynamic stress of congenital heart disease (CHD) might create an electrophysiological and anatomic substrate highly favourable for re-entrant arrhythmias.As a general rule, prescription of antiarrhythmic drugs requires a clear diagnosis with electrocardiographic documentation of a given arrhythmia. Risk-benefit analysis of drug therapy should be considered when facing an arrhythmia in a child. Prophylactic antiarrhythmic drug therapy is given only to protect the child from recurrent supraventricular tachycardia during this time span until the disease will eventually cease spontaneously. In the last decades, radiofrequency catheter ablation is progressively used as curative therapy for tachyarrhythmias in children and patients with or without CHD. Even in young children, procedures can be performed with high success rates and low complication rates as shown by several retrospective and prospective paediatric multi-centre studies. Three-dimensional mapping and non-fluoroscopic navigation techniques and enhanced catheter technology have further improved safety and efficacy even in CHD patients with complex arrhythmias.During last decades, cardiac devices (pacemakers and implantable cardiac defibrillator) have developed rapidly. The pacing generator size has diminished and the pacing leads have become progressively thinner. These developments have made application of cardiac pacing in children easier although no dedicated paediatric pacing systems exist. © 2013 The Author.
Keywords: acebutolol; adenosine; amiodarone; antiarrhythmic agent; atenolol; azimilide; beta adrenergic receptor blocking agent; bisoprolol; digitalis; digoxin; diltiazem; dofetilide; esmolol; flecainide; ibutilide; lidocaine; magnesium sulfate; pindolol; procainaimide; propafenone; propranolol; sotalol; unclassified drug; verapamil; vernakalant; antiarrhythmic activity; article; atrioventricular block; atrioventricular conduction; atrioventricular nodal reentry tachycardia; atrioventricular reentry tachycardia; av nodal conduction block; av nodal conduction block; bidirectional ventricular tachycardia; blurred vision; bradycardia; Brugada syndrome; cardiac resynchronization therapy; cardioversion; catecholaminergic polymorphic ventricular tachycardia; catheter ablation; channelopathy; child care; childhood mortality; clinical effectiveness; congenital heart block; congenital heart disease; congenital heart malformation; consensus; coronary artery; cryoablation; deep sedation; dose response; drug dose reduction; drug excretion; drug half life; drug withdrawal; Ebstein anomaly; ectopic atrial tachycardia; electrical equipment; epicardial pacemaker; evidence based practice; exercise; eye toxicity; Fallot tetralogy; fascicular ventricular tachycardia; fetus heart arrhythmia; follow up; Fontan procedure; genetics; great vessels transposition; heart accessory conduction pathway; heart arrhythmia; atrial fibrillation; heart atrium flutter; heart atrium septum defect; heart electrophysiology; heart failure; heart muscle conduction disturbance; heart muscle conduction system; heart pacing; heart right ventricle dysplasia; heart supraventricular arrhythmia; heart ventricle arrhythmia; heart ventricle tachycardia; human; hyperactivity; hypertrophic cardiomyopathy; hypotension; implantable cardioverter defibrillator; irritability; junctional ectopic tachycardia; late postoperative arrhythmia; lifestyle; liver toxicity; long QT syndrome; lung toxicity; mental disease; narrow QRS tachycardia; narrow QRS tachycardia

Use of diagnostic information submitted to the United Kingdom Central Cardiac Audit Database: Development of categorisation and allocation algorithms - Brown, K.L.; Crowe, S.; Pagel, C.; Bull, C.; Muthialu, N.; Gibbs, J.; Cunningham, D.; Utley, M.; Tsang, V.T.; Franklin, R. (Cardiology in the Young, 2013)
Abstract Objective To categorise records according to primary cardiac diagnosis in the United Kingdom Central Cardiac Audit Database in order to add this information to a risk adjustment model for paediatric cardiac surgery. Design Codes from the International Paediatric Congenital Cardiac Code were mapped to recognisable primary cardiac diagnosis groupings, allocated using a hierarchy and less refined diagnosis groups, based on the number of functional ventricles and presence of aortic obstruction. Setting A National Clinical Audit Database. Patients Children undergoing cardiac interventions: the proportions for each diagnosis scheme are presented for 13,551 first patient surgical episodes since 2004. Results In Scheme 1, the most prevalent diagnoses nationally were ventricular septal defect (13%), patent ductus arteriosus (10.4%), and tetralogy of Fallot (9.5%). In Scheme 2, the prevalence of a biventricular heart without aortic obstruction was 64.2% and with aortic obstruction was 14.1%; the prevalence of a functionally univentricular heart without aortic obstruction was 4.3% and with aortic obstruction was 4.7%; the prevalence of unknown (ambiguous) number of ventricles was 8.4%; and the prevalence of acquired heart disease only was 2.2%. Diagnostic groups added to procedural information: of the 17% of all operations classed as not a specific procedure, 97.1% had a diagnosis identified in Scheme 1 and 97.2% in Scheme 2. Conclusions Diagnostic information adds to surgical procedural data when the complexity of case mix is analysed in a national database. These diagnostic categorisation schemes may be used for future investigation of the frequency of conditions and evaluation of long-term outcome over a series of procedures. © 2012 Cambridge University Press.
Keywords: algorithm; aortic occlusion; article; atrioventricular septal defect; cardiovascular system examination; controlled study; data base; disease classification; Fallot tetralogy; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart surgery; heart ventricle septum defect; human; lung vein drainage anomaly; major clinical study; clinical audit; medical information; patent ductus arteriosus; pediatric surgery; prevalence; quality of life; risk assessment; United Kingdom

Patient and practice factors affecting growth of infants with systemic-to-pulmonary shunt - McCrary, A.W.; Clabby, M.L.; Mahle, W.T. (Cardiology in the Young, 2013)
Abstract Background On recognising poor growth following neonatal palliation with a systemic-to-pulmonary shunt, we sought to determine how patient- and procedure-related factors impact growth, paying attention to the role of the primary cardiologist in this process. Methods In a retrospective review, neonates (133 patients) receiving modified systemic-to-pulmonary artery shunts from 2002 to 2009 were studied and outpatient visits were reviewed. Patients with single- and two-ventricle circulations after shunt takedown were compared using weight-for-age z-score. Results Single-ventricle patients had a higher weight-for-age z-score at neonatal surgery than two-ventricle patients (-0.4 ± 1.0 compared with -1.2 ± 0.9, with p < 0.001), but they had a greater drop in the weight-for-age z-score to the first outpatient visit (-1.1 ± 0.7 compared with -0.8 ± 0.7, with p =0.02). After the first outpatient visit, the weight-for-age z-score was not significantly different between single-ventricle and two-ventricle patients. From multivariate analysis, a lower number of nutritional interventions by cardiologists was significantly associated with poor growth (p =0.03). Poor growth was not associated with race, use of feeding tube, exclusive formula use, or proximity to surgical centre. Conclusion The significant drop in the weight-for-age z-score from neonatal surgery to first outpatient visit suggests that these patients may receive inadequate nutrition. The poorest performers received the least number of outpatient changes to their diet. This finding underscores the critical role of the primary cardiologist in optimising weight gain through adjustments in nutrition. © 2012 Cambridge University Press.
Keywords: article; artificial milk; breast milk; cardiologist; child behavior; child growth; child nutrition; clinical practice; comparative study; controlled study; cyanotic heart disease; diet therapy; female; human; infant; major clinical study; male; medical record review; nasogastric tube; newborn; outpatient care; palliative therapy; pediatric cardiology; race; scoring system; single ventricle cyanotic heart disease; stomach tube; systemic pulmonary shunt; two ventricle cyanotic heart disease; weight for age z score; body weight gain

Erythropoietin neuroprotection in neonatal cardiac surgery: A phase I/II safety and efficacy trial - Andropoulos, D.B.; Brady, K.; Easley, R.B.; Dickerson, H.A.; Voigt, R.G.; Shekerdemian, L.S.; Meador, M.R.; Eisenman, C.A.; Hunter, J.V.; Turcich, M.; Rivera, C.; McKenzie, E.D.; et al. (Journal of Thoracic and Cardiovascular Surgery, 2013)
Objectives: Neonates undergoing complex congenital heart surgery have a significant incidence of neurologic problems. Erythropoietin has antiapoptotic, antiexcitatory, and anti-inflammatory properties to prevent neuronal cell death in animal models, and improves neurodevelopmental outcomes in full-term neonates with hypoxic ischemic encephalopathy. We designed a prospective phase I/II trial of erythropoietin neuroprotection in neonatal cardiac surgery to assess safety and indicate efficacy. Methods: Neonates undergoing surgery for D-transposition of the great vessels, hypoplastic left heart syndrome, or aortic arch reconstruction were randomized to 3 perioperative doses of erythropoietin or placebo. Neurodevelopmental testing using the Bayley Scales of Infant and Toddler Development III was performed at age 12 months. Results: Fifty-nine patients received the study drug. Safety profile, including magnetic resonance imaging brain injury, clinical events, and death, was not different between groups. Three patients in each group died. Forty-two patients (22 in the erythropoietin group and 20 in the placebo group; 79% of survivors) returned for 12-month follow-up. In the group receiving erythropoietin, mean Cognitive Scale scores were 101.1 ± 13.6, Language Scale scores were 88.5 ± 12.8, and Motor Scale scores were 89.9 ± 12.3. In the group receiving placebo, Cognitive Scale scores were 106.3 ± 10.8 (P =.19), Language Scores were 92.4 ± 12.4 (P =.33), and Motor Scale scores were 92.6 ± 14.1 (P =.51). Conclusions: Safety profile for erythropoietin administration was not different than placebo. Neurodevelopmental outcomes were not different between groups; however, this pilot study was not powered to definitively address this outcome. Lessons learned suggest optimized study design features for a larger prospective trial to definitively address the utility of erythropoietin for neuroprotection in this population. © 2013 by The American Association for Thoracic Surgery.
Keywords: NCT00513240; placebo; recombinant erythropoietin; article; Bayley Scales of Infant Development; clinical article; cognition; controlled study; drug efficacy; drug safety; follow up; heart surgery; human; language; motor activity; neuroprotection; newborn; newborn surgery; nuclear magnetic resonance imaging; perioperative period; phase 1 clinical trial; phase 2 clinical trial; priority journal; prospective study; randomized controlled trial

Cardiac performance and quality of life in patients who have undergone the Fontan procedure with and without prior superior cavopulmonary connection - Atz, A.M.; Travison, T.G.; McCrindle, B.W.; Mahony, L.; Glatz, A.C.; Kaza, A.K.; Breitbart, R.E.; Colan, S.D.; Kaltman, J.R.; Margossian, R.; Pasquali, S.K.; Wang, Y.; et al. (Cardiology in the Young, 2013)
Background A superior cavopulmonary connection is commonly performed before the Fontan procedure in patients with a functionally univentricular heart. Data are limited regarding associations between a prior superior cavopulmonary connection and functional and ventricular performance late after the Fontan procedure. Methods We compared characteristics of those with and without prior superior cavopulmonary connection among 546 subjects enrolled in the Pediatric Heart Network Fontan Cross-Sectional Study. We further compared different superior cavopulmonary connection techniques: bidirectional cavopulmonary anastomosis (n equals 229), bilateral bidirectional cavopulmonary anastomosis (n equals 39), and hemi-Fontan (n equals 114). Results A prior superior cavopulmonary connection was performed in 408 subjects (75%); the proportion differed by year of Fontan surgery and centre (p-value less than 0.0001 for each). The average age at Fontan was similar, 3.5 years in those with superior cavopulmonary connection versus 3.2 years in those without (p-value equals 0.4). The type of superior cavopulmonary connection varied by site (p-value less than 0.001) and was related to the type of Fontan procedure. Exercise performance, echocardiographic variables, and predominant rhythm did not differ by superior cavopulmonary connection status or among superior cavopulmonary connection types. Using a test of interaction, findings did not vary according to an underlying diagnosis of hypoplastic left heart syndrome. Conclusions After controlling for subject and era factors, most long-term outcomes in subjects with a prior superior cavopulmonary connection did not differ substantially from those without this procedure. The type of superior cavopulmonary connection varied significantly by centre, but late outcomes were similar. © 2012 Cambridge University Press.
Keywords: NCT00132782; anticoagulant agent; dipeptidyl carboxypeptidase inhibitor; diuretic agent; adolescent; adult; article; cardiopulmonary bypass; cardiovascular parameters; cavopulmonary connection; child; chylothorax; cross-sectional study; disease association; echocardiography; Fontan procedure; heart performance; heart rhythm; human; hypoplastic left heart syndrome; major clinical study; outcome assessment; preschool child; quality of life; school child

A case of wolf-hirschhorn syndrome and hypoplastic left heart syndrome - Von Elten, K.; Sawyer, T.; Lentz-Kapua, S.; Kanis, A.; Studer, M. (Pediatric Cardiology, 2013)
Wolf-Hirschhorn Syndrome (WHS) is a genetic syndrome that includes a typical facial appearance, mental retardation, growth delay, seizures, and congenital cardiac defects. A deletion of the terminal band of the short arm of chromosome 4, with a breakpoint at the 4p15 to 4p16 region, is the most common genetic mutation causing WHS. Congenital heart disease associated with WHS typically includes atrial and ventricular septal defects, though there are a few case reports of associated complex congenital heart disease. Here we report a case of an infant with a large 4p deletion, with a breakpoint at the 4p12 region, and hypoplasic left heart syndrome. We discuss a possible link between the size of the chromosomal deletion in WHS and the severity of the cardiac defect. © 2012 Springer Science+Business Media, LLC (outside the USA).
Keywords: article; case report; chromosome deletion 4; congenital heart disease; disease severity; gene mutation; human; hypoplastic left heart syndrome; infant; Wolf Hirschhorn syndrome

Home-based rehabilitation enhances daily physical activity and motor skill in children who have undergone the fontan procedure - Longmuir, P.E.; Tyrrell, P.N.; Corey, M.; Faulkner, G.; Russell, J.L.; McCrindle, B.W. (Pediatric Cardiology, 2013)
This randomized trial compared physical activity enhancing exercise prescription and education programs in 61 children (36 male) with single-ventricle physiology after Fontan. After Fontan, children are less active than recommended for optimal health. They are often geographically dispersed and unable to attend weekday programs. Participants, 5.9-11.7 years of age who were status 5.3 years post-Fontan, received 12-month, parent-delivered home programs to enhance physical activity, motor skill, fitness, and activity attitudes. Daily moderate-to-vigorous physical activity (MVPA) was measured at baseline and again at 6, 12, and 24 months. Secondary outcomes were gross motor skill, fitness, and activity attitudes. Gross motor skill (p =.01) was significantly greater at the end of the 2-year study period for both intervention groups combined. MVPA at 2 years was significantly greater (p =.03) than the predicted decrease with age. Spring season (85 ± 25 min), male sex (69 ± 21 min), greater baseline activity (0.3 ± 0.1 min/baseline minute), and better gross motor skill (1.1 ± 0.4 min/percentile) increased weekly MVPA in a multivariable repeated-measures regression model adjusted for intervention, maturation during the 2-year study, sex, season, and baseline activity. Benefits were not influenced by type of rehabilitation, compliance, or rural/urban location. Home-based, pediatric physical activity rehabilitation enhances physical activity, gross motor skill, exercise capacity, and physical fitness among preadolescent children after Fontan regardless of rural/urban location. Prescribed education and exercise programs are similarly effective for providing the important health benefits of daily physical activity. Enhanced gross motor skill is associated with increased MVPA despite exercise capacity limitations after Fontan. Rehabilitation attenuates the expected decrease in MVPA with age. © 2013 Springer Science+Business Media New York.
Keywords: adolescent; article; child; controlled study; education program; exercise; female; fitness; Fontan procedure; gender; heart rehabilitation; heart single ventricle; home care; human; major clinical study; male; motor performance; multivariate analysis; outcome assessment; patient compliance; physical activity; preschool child; randomized controlled trial; regression analysis; rural area; school child; spring; urban area

Surgical strategy for atrioventricular septal defect and tetralogy of fallot or double-outlet right ventricle - Raju, V.; Burkhart, H.M.; Rigelman Hedberg, N.; Eidem, B.W.; Li, Z.; Connolly, H.; Schaff, H.V.; Dearani, J.A. (Annals of Thoracic Surgery, 2013)
Background: Tetralogy of Fallot, or double-outlet right ventricle with atrioventricular (AV) septal defect (TOF/DORV-AVSD), is rare, with limited long-term data available. We report our institutional experience and outcome over a 50-year period. Methods: From January 1961 to January 2011, 73 patients (50 males [68%]), with a mean age of 6.8 ± 4.4 years (range, 1 month to 35 years), underwent surgical repair of TOF/DORV-AVSD. Symptoms included cyanosis in 50 (69%) and heart failure in 12 (17%). Down syndrome was present in 25 (34%). Rastelli type A, B, and C was seen in 12%, 7%, and 81% of patients, respectively. Moderate or more common AV valve (AVV) regurgitation was present in 40%. Forty-nine patients (67%) had previous palliation, including 36 with a systemic-to-pulmonary arterial shunt. Results: Surgical management included two-ventricle complete repair (CR) in 35 (48%) and single-ventricle (SV) palliation in 38 (52%). Overall, early mortality was 31% for CR and 34% for SV; after 1990, mortality was 6% for CR and 14% for SV. Repair before 1990 (p = 0.008) and the presence of significant common AVV regurgitation (p = 0.016) were univariate risk factors for early death in both groups. Median follow-up was 9.8 years (maximum, 32 years). Late mortality rate was 12% in CR (n = 6) and 18% (n = 9) in SV (p = 0.95). The presence of significant right AVV regurgitation was associated with late death (p = 0.02). Overall survival at 1, 5, and 15 years was 92%, 77%, and 77% in CR, and 83%, 79%, 70% in SV (p = 0.9). Freedom from reoperation at 1, 5, and 15 years was 95%, 85%, 67% in CR and 96%, 91%, 82% in SV (p = 0.1). Reoperations were most common for right ventricular outflow tract pathology, Fontan revision, and AVV intervention. Right AVV regurgitation (p = 0.018) and repair before 1990 (p = 0.041) were risk factors for late reoperation in both groups. Conclusions: Complete repair of TOF/DORV-AVSD is standard of care and associated with low early mortality rate in the current era, with reasonable long-term outcome. SV palliation continues to have significant risk. The presence of AVV regurgitation is a significant risk factor for death and reoperation. © 2013 The Society of Thoracic Surgeons.
Keywords: adult; article; atrioventricular septal defect; cardiovascular mortality; cardiovascular risk; cardiovascular surgery; child; disease severity; Down syndrome; Fallot tetralogy; female; follow up; heart right ventricle double outlet; heart right ventricle outflow tract; heart single ventricle; heart valve regurgitation; human; infant; major clinical study; male; overall survival; palliative therapy; preschool child; priority journal; reoperation; school child

Self-reported health status (EQ-5D) in adults with congenital heart disease - Berghammer, M.; Karlsson, J.; Ekman, I.; Eriksson, P.; Dellborg, M. (International Journal of Cardiology, 2013)
Purpose Today, more patients with congenital heart disease (CHD) reach adulthood. There are conflicting findings concerning the relationship between quality of life (QoL) or health state for adults with CHD and the complexity of their CHD. The aim of the study was, firstly, to compare the reported health status and health perception of adult patients with CHD and, secondly, to investigate what variables influenced the patients' health status and health perception. Methods Data from 1435 patients completing the EQ-5D questionnaire, which includes reported health status and health perception, were analyzed. Results Valid EQ-5D data were reported by 1274 patients, showing overall results indicating a good health status. Problems were most frequently reported in the dimension "pain/discomfort" (31.9%) and "anxiety/depression" (29.8%). Higher occurrence of problems were reported by patients with complex disease i.e. single ventricle (p < 0.001) and by female patients (p < 0.0001). Symptomatic patients reported a lower health status (p < 0.0001) and a lower perceived health on EQ-VAS (p < 0.0001). Of the asymptomatic patients, 20.5% nevertheless reported problems in "pain/discomfort" and 22.2% in the "anxiety/depression" dimension. Conclusion The health status of adults with CHD is influenced by symptoms, NYHA-classification, age and gender. Adults with CHD report a lower occurrence of problems in comparison to previously published results from a general population, but the importance of actively asking about the patient's experience is demonstrated by the high degree of asymptomatic patients reporting problems on EQ-5D.
Keywords: adolescent; adult; aged; anxiety; aortic arch anomaly; aortic valve disease; article; asymptomatic disease; congenital heart disease; controlled study; depression; disease registry; dyspnea; edema; faintness; Fallot tetralogy; fatigue; female; Health Perceptions Questionnaire; health status; heart palpitation; human; major clinical study; male; mitral valve disease; priority journal; pulmonary valve disease; quality of life; questionnaire; self care; self report; symptom; thorax pain; tricuspid valve disease; very elderly; visual analog scale

Prognosis of children with cardiomyopathy submitted to fontan surgery: 30 years of experience at the Hospital Infantil de México Federico Gómez - Bolio-Cerdán, A.; Ruiz-González, S.; Romero-Cárdenas, P.; Hernández-Morales, G.; Villasís-Keever, M.A. (Boletin Medico del Hospital Infantil de Mexico, 2013)
Background. At the present time, the Fontan procedure is indicated for patients with univentricular cardiac pathology. In Mexico, few tertiary centers are performing Fontan surgery in the pediatric population. The objective was to analyze the results of patients with congenital heart disease with univentricular physiology who have undergone Fontan surgery since 1980 in the Hospital Infantil de Mexico Dr. Federico Gomez. Methods. We present a retrospective analysis of pediatric patients undergoing Fontan surgery. We included variables related to preoperative mortality and morbidity, those related to surgery and to the postoperative period. A bivariate analysis with the comparison of averages and odds ratio was performed. Kaplan-Meier survival curves were constructed. Results. From 1983 to 2012, 53 Fontan surgeries have been performed. Of the total, comprehensive data of 32 patients were gathered. The most common congenital heart anomaly was tricuspid atresia IB (39.4%); according to type of surgery, in 48% of patients extracardiac Fontan was performed followed by intracardiac Fontan (24%). In 87% of patients fenestration was performed. The most common complications were acute renal failure, neurological problems and pleural effusion. Overall survival was 65.6%; 90.9% of patients died within the first month of surgery. Patients have been reported with >20 years of survival (average actuarial survival 14.5 years). Variables associated with mortality were younger age at surgery, type of Fontan performed, surgical technique complications, lack of fenestration and acute renal failure. Conclusions. Evolution of Fontan surgery during the past 30 years has been satisfactory. In patients undergoing this procedure, mortality and quality of life have shown improvements.
Keywords: acute kidney failure; article; cardiomyopathy; cardiovascular mortality; clinical article; Fontan procedure; human; morbidity; neurologic disease; overall survival; pleura effusion; postoperative period; prognosis; retrospective study; tricuspid valve atresia

Self-reported health status (EQ-5D) in adults with congenital heart disease - Berghammer, M.; Karlsson, J.; Ekman, I.; Eriksson, P.; Dellborg, M. (International Journal of Cardiology, 2013)
Purpose: Today, more patients with congenital heart disease (CHD) reach adulthood. There are conflicting findings concerning the relationship between quality of life (QoL) or health state for adults with CHD and the complexity of their CHD. The aim of the study was, firstly, to compare the reported health status and health perception of adult patients with CHD and, secondly, to investigate what variables influenced the patients' health status and health perception. Methods: Data from 1435 patients completing the EQ-5D questionnaire, which includes reported health status and health perception, were analyzed. Results: Valid EQ-5D data were reported by 1274 patients, showing overall results indicating a good health status. Problems were most frequently reported in the dimension "pain/discomfort" (31.9%) and "anxiety/ depression" (29.8%). Higher occurrence of problems were reported by patients with complex disease i.e. single ventricle (p < 0.001) and by female patients (p < 0.0001). Symptomatic patients reported a lower health status (p < 0.0001) and a lower perceived health on EQ-VAS (p < 0.0001). Of the asymptomatic patients, 20.5% nevertheless reported problems in "pain/discomfort" and 22.2% in the "anxiety/depression" dimension. Conclusion: The health status of adults with CHD is influenced by symptoms, NYHA-classification, age and gender. Adults with CHD report a lower occurrence of problems in comparison to previously published results from a general population, but the importance of actively asking about the patient's experience is demonstrated by the high degree of asymptomatic patients reporting problems on EQ-5D. © 2011 Elsevier Ireland Ltd.
Keywords: adolescent; adult; article; congenital heart disease; controlled study; disease association; disease classification; dyspnea; edema; educational status; Euro QoL 5 Dimension questionnaire; faintness; fatigue; female; health status; heart palpitation; human; life satisfaction; major clinical study; male; mental function; perception; priority journal; quality of life; questionnaire; self care; self report; symptomatology; thorax pain; validation process; visual analog scale

The effect of Bosentan on exercise capacity in Fontan patients; rationale and design for the TEMPO study - Hebert, A.; Jensen, A.S.; Idorn, L.; Sørensen, K.E.; Søndergaard, L. (BMC Cardiovascular Disorders, 2013)
Background: Palliative treatment with the Fontan procedure has greatly improved survival for children with functionally univentricular heart. Since Fontan performed the first successful operation, the procedure has evolved and is now performed as Total Cavo-Pulmonary Connection (TCPC).An increasing prevalence and longer life expectancy of TCPC patients have raised new challenges. The survivors are often suffering complications such as arrhythmias, myocardial dysfunction, thromboembolic events, neuropsychological deficit, protein-losing enteropathy and reduced exercise capacity. Several causes for the reduced exercise capacity may be present e.g. impaired function of the single ventricle, valve dysfunction and chronotropic impairment, and perhaps also increased pulmonary vascular resistance. Thus, plasma endothelin-1 has been shown to correlate with increased pulmonary vascular resistance and the risk of failing Fontan circulation. This has raised the question of the role for pulmonary vasodilation therapy, especially endothelin receptor antagonist in the management of TCPC patients.Methods/Design: The TEMPO trial aims to investigate whether Bosentan, an endothelin receptor antagonist, can be administered safely and improve exercise capacity in TCPC patients. The trial design is randomized, double-blind and placebo-controlled. Bosentan/placebo is administered for 14 weeks with control visits every four weeks. The primary endpoint is change in maximal oxygen consumption as assessed on bicycle ergometer test. Secondary endpoints include changes in pulmonary blood flow during exercise test, pro brain natriuretic peptide and quality of life.Discussion: We hypothesize that treatment with Bosentan, an endothelin receptor antagonist, can be administered safely and improve exercise capacity in TCPC patients.Trial registration: clinicaltrials.gov NCT01292551. © 2013 Hebert et al.; licensee BioMed Central Ltd.
Keywords: NCT01292551; aspartate aminotransferase; bilirubin; bosentan; brain natriuretic peptide; endothelin receptor antagonist; hemoglobin; placebo; adolescent; aminotransferase blood level; article; bicycle ergometry; bilirubin blood level; child; controlled study; double blind procedure; drug safety; drug withdrawal; exercise; female; Fontan procedure; heart single ventricle; hematocrit; hemoglobin blood level; human; lung blood flow; major clinical study; male; multicenter study; oxygen consumption; oxygen saturation; priority journal; protein analysis; quality of life; randomized controlled trial; school child; side effect; surgical patient; systolic blood pressure; platelet count; total cavopulmonary connection; treatment outcome

Mechanical support as failure intervention in patients with cavopulmonary shunts (MFICS): Rationale and aims of a new registry of mechanical circulatory support in single ventricle patients - Rossano, J.W.; Woods, R.K.; Berger, S.; Gaynor, J.W.; Ghanayem, N.; Morales, D.L.S.; Ravishankar, C.; Mitchell, M.E.; Shah, T.K.; Mahr, C.; Tweddell, J.S.; Adachi, I.; et al. (Congenital Heart Disease, 2013)
It is now recognized that a majority of single ventricle patients, those with functionally univentricular hearts, who have survived palliative cavopulmonary connection will experience circulatory failure and end-organ dysfunction due to intrinsic inadequacies of a circulation supported by a single ventricle. Thus, there are an increasing number of patients with functional single ventricles presenting with failing circulations that may benefit from mechanical circulatory support (MCS). The paucity of experience with MCS in this population, even at high volume cardiac centers, contributes to limited available data to guide MCS device selection and management. Thus, a registry of MCS in this population would be beneficial to the field. A conference was convened in January 2012 of pediatric and adult cardiologists, pediatric cardiac intensivists, congenital heart surgeons, and adult cardiothoracic surgeons to discuss the current state of MCS, ventricular assist device, and total artificial heart therapy for patients who have undergone cavopulmonary connection, either superior cavopulmonary connection or total cavopulmonary connection. Specifically, individual experience and challenges with VAD therapy in this population was reviewed and creation of a multiinstitutional registry of MCS/ventricular assist device in this population was proposed. This document reflects the consensus from the meeting and provides a descriptive overview of the registry referred to as Mechanical Support as Failure Intervention in Patients with Cavopulmonary Shunts. © 2013 Wiley Periodicals, Inc.
Keywords: article; artificial heart; assisted circulation; biventricular assist device; cavopulmonary connection; clinical effectiveness; congenital heart disease; heart transplantation; human; ischemia; left ventricular assist device; mechanical circulatory support; pediatrician; priority journal; quality of life; right ventricular assist device; surgeon; thorax surgery; ventricular assist device

Lymphoscintigraphy in plastic bronchitis, A pediatric case report - Ezmigna, D.R.; Morgan, W.J.; Witte, M.H.; Brown, M.A. (Pediatric Pulmonology, 2013)
Plastic bronchitis (PB) is an uncommon, potentially fatal disease, marked by endobronchial cast formation causing variable degrees of respiratory distress. Primary and secondary pulmonary lymphatic abnormalities have been identified among the underlying mechanisms of cast formation. We present a case of PB where lymphoscintigraphy demonstrated the underlying lymphatic defect. A 6-year-old Hispanic male with congenital heart disease (CHD; post-Fontan) presented with recurrent pneumonia, respiratory distress. Bronchoscopy showed inflamed hypervascular mucosa and thick mucus plugs; no casts were seen. Later, PB was diagnosed after the patient expectorated a bronchial cast. Cast analysis showed lymphocytic aggregates with mucin and fibrin. Lymphoscintigraphy revealed abnormal lymphatic collaterals and retrograde trace reflux into the superior mediastinum, a picture consistent with thoracic duct lymph leakage into the tracheobronchial tree. The pathogenesis of PB is not fully understood, especially in patients with CHD. Chyle in bronchial casts suggests abnormal lymphatic flow. Reports of lymph flow abnormalities, especially endobronchial lymph leakage in CHD are limited. Lymphoscintigraphy in our case demonstrated clear evidence of retrograde lymph reflux and leakage into the bronchial tree. The case presented suggests that in some patients following Fontan surgery, high intrathoracic lymphatic pressure and retrograde lymph flow may contribute to recurrent cast formation. Finding the underlying lymphatic abnormality helps in specific case management. Lymphoscintigraphy is a safer and easier method than lymphangiography. Surgical lymphatic-venous shunting may be possible in select cases. © 2012 Wiley Periodicals, Inc.
Keywords: fibrin; mucin; article; bronchitis; bronchoscopy; case report; child; child health care; congenital heart disease; Fontan procedure; heart disease; human; lymph flow; lymphangiography; lymphoscintigraphy; lymphovenous anastomosis; male; pathogenesis; plastic bronchitis; pneumonia; preschool child; priority journal; respiratory distress; thoracic duct; tracheobronchial tree

In favor of the hybrid stage 1 as the initial palliation for hypoplastic left heart syndrome - Galantowicz, M. (Seminars in Thoracic and Cardiovascular Surgery: Pediatric Cardiac Surgery Annual, 2013)
There are many reasons to consider using the Hybrid Stage 1 procedure as the initial palliation for hypoplastic left heart syndrome. It allows all options for treatment, including a delayed traditional approach, as well as a platform to evolve our overall approach to this challenging heart defect. © 2013 Elsevier Inc.
Keywords: article; borderline left heart structure; cohort analysis; cost; evidence based practice; extracorporeal oxygenation; Fontan procedure; heart catheterization; heart surgery; heart transplantation; heart ventricle function; hemodynamics; hospitalization; human; hybrid stage 1; hypoplastic left heart syndrome; intermethod comparison; lung artery banding; Norwood procedure; outcome assessment; overall survival; palliative therapy; pediatrics; quality of life; right ventricle to pulmonary artery conduit; surgical mortality; treatment indication

1q21.1 Microduplication expression in adults - Dolcetti, A.; Silversides, C.K.; Marshall, C.R.; Lionel, A.C.; Stavropoulos, D.J.; Scherer, S.W.; Bassett, A.S. (Genetics in Medicine, 2013)
Purpose:Rare, recurrent chromosome 1q21.1 duplications have been associated with developmental delay, congenital anomalies, and macrocephaly in children. Data on adult clinical expression would help to inform genetic counseling.Methods:A systematic review of 22 studies reporting 107 individuals (59 children and 48 adults) with 1q21.1 duplications was conducted. We compiled the available phenotypic data to attempt to identify the most highly associated clinical features and to determine expression in adults. We also report on seven adult cases newly identified in the studies of schizophrenia and tetralogy of Fallot at our center.Results:Five cases were ascertained as controls, 32 as relatives of probands, and 70 as having clinical features: autism spectrum disorder (n = 15), congenital heart disease (n = 12), schizophrenia (n = 10), or other, mostly developmental, features (n = 33). The 1q21.1 duplication was significantly enriched in the cohorts with schizophrenia (P = 0.0155) and tetralogy of Fallot (P = 0.0040) at our center as compared with controls. There was a paucity of clinical data for adults; the most common features, other than those used for ascertainment, included macrocephaly and abnormalities of possible connective tissue origin (e.g., carpal tunnel syndrome).Conclusion: Further data are needed to characterize lifetime expression of 1q21.1 duplications. These initial results, however, suggest that anticipatory care should include attention to later-onset conditions such as schizophrenia.
Keywords: article; attention deficit disorder; autism; bipolar disorder; carpal tunnel syndrome; cataract; cholelithiasis; chromosome 1q; chromosome duplication; congenital heart disease; congenital malformation; craniofacial malformation; deep vein thrombosis; depression; developmental disorder; Fallot tetralogy; gene expression; head circumference; heart disease; heart single ventricle; heart ventricle septum defect; human; hypercholesterolemia; intellectual impairment; macrocephaly; non insulin dependent diabetes mellitus; schizophrenia; sex ratio; systematic review

Myocardial perfusion abnormalities in patients occurring more than 1 year after successful univentricular (fontan surgery) and biventricular repair (complete repair of tetralogy of fallot) - Priyadarshini, A.; Saxena, A.; Patel, C.; Paul, V.K.; Lodha, R.; Airan, B. (Pediatric Cardiology, 2013)
The outcome of children born with cyanotic congenital heart disease has markedly improved over the years. Follow up is recommended for most post-operated cases as complications may occur over long term. One of the complications is the development of ventricular dysfunction, often seen after a successful Fontan surgery (or one of its modifications) for single ventricle. The aim of this study was to determine the prevalence of myocardial perfusion abnormalities in the ventricular myocardium of asymptomatic patients, older than 8 years of age, who had earlier undergone either a univentricular palliation (modified Fontan procedure) or a biventricular repair for tetralogy of Fallot, more than a year ago. All eligible patients underwent screening electrocardiogram (to rule out rhythm disturbance) and echocardiography. Patients with ventricular ejection fraction of more than 50 % by echocardiography were included. Enrolled patients were subjected to gated stress-rest myocardial perfusion imaging using Technitium-99m tetrofosmin single photon emission-computerized tomography (SPECT). Ventricular ejection fraction was also calculated from gated rest study. For the Fontan group, we also analyzed data to see if the morphology of the systemic ventricle would make a difference as far as myocardial perfusion was concerned. Twenty-six patients were enrolled (11 had undergone Fontan surgery and 15 had complete repair of tetralogy of Fallot). Seven of 11 patients in the Fontan group had myocardial perfusion defects (63.6 %) as against none in the repaired tetralogy of Fallot group (p < 0.001). The ejection fraction was within normal range in both the groups; it was statistically higher in the post tetralogy of Fallot repair group (p < 0.04). There were two subgroups in the post Fontan group depending on the morphology of systemic ventricle-left (4 patients) and non-left (7 patients). Higher number and larger size of perfusion defects were present in the non-left ventricular systemic ventricle morphology as compared with left ventricular morphology, but this difference did not reach statistical significance. Myocardial perfusion defects are common in patients who have undergone univentricular repair more than one year ago in contrast to patients who had a biventricular repair for tetralogy of Fallot. In the Fontan group, the morphology of the systemic ventricle was not predictive of prevalence of perfusion defect. © 2012 Springer Science+Business Media New York.
Keywords: tetrofosmin tc 99m; absence of side effects; adolescent; adult; article; cardiac imaging; child; clinical article; controlled study; cross-sectional study; echocardiography; electrocardiography; Fallot tetralogy; female; Fontan procedure; heart ejection fraction; heart muscle perfusion; heart single ventricle; human; male; myocardial perfusion imaging; palliative therapy; PET scanner; prospective study; school child; single photon emission computed tomography; Infinia Hawkeye

Congenital heart disease in elementary school children in rural Thailand: The role of the trained noncardiologist - Cholkraisuwat, E.; Buddharaksa, Y.; Sayasathid, J. (Asian Biomedicine, 2013)
Background: Congenital heart diseases (CHD) comprise about one-third of all major birth defects. Children with delayed diagnosis and improper treatment are at a high risk of morbidity and mortality. Objective: To determine the prevalence of unrecognized congenital heart disease among elementary school students and study the types and frequency of congenital heart disease in Phitsanulok, Pichit, and Kampangpetch provinces of Thailand using trained nurses and other health care personnel. Methods: Between September 2008 and September 2010, 138,529 students from 1,243 elementary schools were screened for abnormal heart conditions by trained nurses or health care workers. The students who were suspected to have CHD were referred to a pediatric cardiologist for complete evaluation and identification of the lesions. Results: Five hundred forty eight students were suspected to have heart diseases and 102 students were diagnosed as CHD. The average prevalence of unrecognized CHD in Phitsanulok, Pichit, and Kampangpetch was 0.74 per 1,000. Simple acyanotic lesions (ventricular septal defect, atrial septal defect, and pulmonary stenosis) were common in this study (32.35%, 16.67%, and 11.76%, respectively). Conclusion: Qualified nurses or health care workers can be useful for identifying patients with CHD. The role of these personnel in the national heart screening program should be further clarified.
Keywords: adolescent; aortic stenosis; aortic regurgitation; article; cardiologist; child; collateral circulation; congenital heart disease; dextrocardia; Ebstein anomaly; Fallot tetralogy; health care personnel; health program; heart atrium septum defect; heart right ventricle double outlet; heart surgery; heart ventricle septum defect; human; hypertrophic obstructive cardiomyopathy; major clinical study; mitral valve regurgitation; nurse; patent ductus arteriosus; preschool child; prevalence; primary school; pulmonary artery stenosis; pulmonary valve atresia; pulmonary valve insufficiency; pulmonary valve stenosis; quality of life; rural area; school child; Thailand; tricuspid valve atresia; tricuspid valve regurgitation; ventricular noncompaction

Prevalence, pattern and outcome of congenital heart disease in Bhabha Atomic Research Centre Hospital, Mumbai - Sawant, S.P.; Amin, A.S.; Bhat, M. (Indian Journal of Pediatrics, 2013)
Objective: To assess the prevalence, pattern and outcome of congenital heart disease (CHD) among the babies born in Bhabha Atomic Research Centre (BARC) Hospital, Mumbai and to compare the pattern of CHD with the study done in the same hospital in year 1999. Methods: A prospective, longitudinal study was conducted from January 2006 through December 2011. Babies presenting with murmur were closely followed up till the diagnosis and further to assess the outcome. 2-D Echocardiography was used as a diagnostic tool. Results: The overall prevalence of CHD was 13.28 per 1,000 live births. Ventricular septal defect (VSD) was the commonest CHD (42.86 %) followed by Atrial septal defect (ASD) (25.71 %) giving the prevalence of 5.69 and 3.41 per 1,000 live births respectively. Tetrology of Fallot's (TOF) was the main cyanotic CHD (8.57 %) with the prevalence of 1.13 per 1,000 live births. VSD and TOF were prevalent in males. ASD was prevalent in females. Associated structural anomalies were detected in 22.86 % cases; Down's syndrome being the commonest.Spontaneous closure rate of 71.4 % in muscular VSD and 50 % in perimembranous VSD was observed. All small sized VSD's closed spontaneously and all large sized VSD's required surgical intervention. Spontaneous closure was observed in 44.44 % of ASD cases. Overall, device closure was required in 17.14 % and 25.71 % underwent open heart surgery. Conclusions: The pattern of CHD has remained almost the same compared to the previous study. The outcome was excellent due to early diagnosis, regular follow up and timely intervention. © 2012 Dr. K C Chaudhuri Foundation.
Keywords: aortic coarctation; article; congenital heart disease; Down syndrome; Fallot tetralogy; female; follow up; great vessels transposition; heart atrium septum defect; heart murmur; heart ventricle septum defect; human; India; live birth; longitudinal study; lung vein drainage anomaly; major clinical study; male; newborn; outcome assessment; patent ductus arteriosus; prevalence; prospective study; pulmonary valve stenosis; tricuspid valve atresia; two dimensional echocardiography

Living at altitude adversely affects survival among patients with a fontan procedure - Johnson, J.T.; Lindsay, I.; Day, R.W.; Van Dorn, C.S.; Hoffman, J.; Everitt, M.D.; Yetman, A.T. (Journal of the American College of Cardiology, 2013)
Objectives: This study sought to determine whether survival in this cohort of patients was adversely affected by increased residential altitude. Background: The success of the Fontan procedure depends in large part on low pulmonary vascular resistance (PVR). Factors that increase PVR, including an increase in residential altitude, may adversely affect long-term outcome. Higher altitude has been shown to affect functional well-being in patients with a Fontan circulation. Methods: Databases from a tertiary cardiac care center in the Intermountain West (elevation 5,000 feet) were analyzed for patients born with single-ventricle anatomy who would now be of adult age. Complete data were then collected on all identified patients who subsequently underwent the Fontan operation. Correlates of, and time to, adverse outcome, defined as death, cardiac transplantation, or clinical decompensation requiring a move to sea level, were determined. Results: Of 149 patients with single-ventricle anatomy, 103 underwent the Fontan procedure, with 70 surviving to adulthood at moderate altitude. Adverse outcome occurred in 55, with death in 24 (23%), cardiac transplantation in 18 (17%), and clinical decompensation requiring move to sea level in 13 (13%). There was no relationship between type, age at, or era of Fontan procedure and long-term outcome. Correlates of long-term, transplant-free survival at moderate altitude included lower residential altitude (4,296 vs. 4,637 feet, p < 0.001), and lower pulmonary artery pressures before the Fontan procedure (13 vs. 15 mm Hg, p = 0.01), and after (14 vs. 18 mm Hg, p = 0.01). Conclusions Long-term outcome after the Fontan procedure is adversely impacted by higher residential altitude. © 2013 by the American College of Cardiology Foundation.
Keywords: adolescent; adult; altitude; article; child; cohort analysis; female; Fontan procedure; heart failure; heart single ventricle; heart transplantation; human; liver dysfunction; lung artery pressure; lung vascular resistance; major clinical study; male; mortality; outcome assessment; priority journal; residential altitude; retrospective study; risk factor; survival; thrombosis; treatment failure

Neonatology in the United States: Where we are, and where we are going - Meadow, W. (Current Pediatric Reviews, 2013)
The United States is the largest country in the 'industrialized world', and, as such, has dominated the medical literature reporting practices and outcomes of neonatal intensive care. Perhaps surprisingly, very few things about U.S. Neonatology are unique to the U.S. This chapter will attempt an impossible task - summarizing the practice of neonatology in the entire U.S. I will draw parallels to practices of my colleagues around the globe, and point out American idiosyncracies where they arise. I will end with my sense of the likely (at least in the near-term) future developments for neonatology in the U.S. © 2013 Bentham Science Publishers.
Keywords: antibiotic agent; article; congenital malformation; Down syndrome; ethnicity; futurology; gestational age; history; human; hypoplastic left heart syndrome; legal abortion; meningomyelocele; neonatology; newborn care; newborn intensive care; newborn morbidity; newborn mortality; prenatal diagnosis; priority journal; trisomy 13; trisomy 18; United States; ventilator

Perioperative management of shock in two fontan patients with plastic bronchitis - Singhal, N.R.; Da Cruz, E.M.; Nicolarsen, J.; Schwartz, L.I.; Merritt, G.R.; Barrett, C.; Twite, M.D.; Ing, R.J. (Seminars in Cardiothoracic and Vascular Anesthesia, 2013)
Plastic bronchitis is potentially a life-threatening complication of long-standing surgically palliated single ventricle congenital heart disease. Patients can present with hypoxia requiring urgent bronchoscopy for removal of bronchial casts. Perioperative care for these patients is challenging and anesthesia is associated with significant cardiac risk. As more surgically corrected single ventricle patients survive to adulthood, these patients are expected to present more frequently. This report details the perioperative management of 2 Fontan patients with hypoxia and significant plastic bronchitis disease burden. © The Author(s) 2013.
Keywords: epinephrine; alteplase; antibiotic agent; bronchodilating agent; ceftriaxone; dopamine; enalapril; fentanyl; heparin; hydrocortisone sodium succinate; hypertensive agent; ketamine; methylprednisolone; midazolam; noradrenalin; propofol; sevoflurane; sildenafil; vasopressin; agitated depression; airway obstruction; article; artificial ventilation; bronchitis; bronchoscopy; case report; child; coughing; croupous bronchitis; disease association; drug dose titration; echocardiography; electrocardiography; endotracheal intubation; extracorporeal oxygenation; female; fever; first degree atrioventricular block; Fontan procedure; hematothorax; histopathology; human; hypoplastic left heart syndrome; hypotension; hypoxemia; hypoxia; intensive care unit; laryngeal mask; male; oxygen therapy; perioperative period; physical examination; physiotherapy; pleura effusion; pulse oximetry; resuscitation; school child; septal occluder; shock; surgical patient; tachypnea; thorax radiography; tracheobronchitis; tricuspid valve atresia; upper respiratory tract infection; LMA

Use of aerosolized tissue plasminogen activator in the treatment of plastic bronchitis - Lubcke, N.L.; Nussbaum, V.M.; Schroth, M. (Annals of Pharmacotherapy, 2013)
OBJECTIVE: To present a case of nebulized tissue plasminogen activator (t-PA) treatment for symptomatic plastic bronchitis in a pediatric patient years after a Fontan procedure. CASE SUMMARY: A 13-year-old boy with a history of corrected congenital heart disease was admitted to the pediatric intensive care unit after 2 weeks of worsening respiratory distress. A chest radiograph and subsequent bronchoscopy revealed extensive mucus plugging due to plastic bronchitis. Casts reaccumulated quickly after manual removal of the mucus and a regimen of aerosolized t-PA was initiated to break down the casts and prevent further cast formation over the 17-day hospital course. The treatment was successful and the patient was discharged home without evidence of bronchial casts. DISCUSSION: Plastic bronchitis is a potentially devastating condition in which pulmonary infiltrates line the bronchial tree, forming casts and prohibiting effective oxygen exchange. There are few effective treatment options for this condition. The use of aerosolized t-PA for the treatment of plastic bronchitis has been reported to be safe and effective in 4 cases but no consistent regimen, dose, or duration of treatment has been established. CONCLUSIONS: t-PA can be nebulized and inhaled for successful inhibition of bronchial cast formation. More information to determine the most effective dose and duration of therapy is needed to effectively improve the lives of people with plastic bronchitis. © 1967-2013 Harvey Whitney Books Co. All rights reserved.
Keywords: azithromycin; ceftriaxone; dornase alfa; fibrin; oxygen; salbutamol; tissue plasminogen activator; adolescent; article; atelectasis; bronchitis; bronchoscopy; case report; cyanosis; emergency ward; Fontan procedure; hemidiaphragm; human; inflammatory infiltrate; loading drug dose; lung extravascular fluid; male; mediastinum disease; nebulization; oxygen saturation; oxygen therapy; plastic bronchitis; priority journal; respiratory distress; spirometry; thorax pain; thorax radiography; treatment outcome

Social impact on families of children with complex congenital heart disease - Almesned, S.; Al-Akhfash, A.; Al Mesned, A. (Annals of Saudi Medicine, 2013)
BACKGROUND AND OBJECTIVES: The care of children with complex congenital heart disease creates emotional and financial hardships for their families. We evaluated the social impact on families of patients with complex congenital heart disease (CHD) who underwent single ventricle repair. DESIGN AND SETTING: Cross-sectional survey conducted at the pediatric cardiology outpatient department at Prince Sultan Cardiac Center-Qassim (PSCC-Q). PATIENTS AND METHODS: All patients diagnosed and treated for complex CHD of single ventricle pathophysiology and seen in the pediatric cardiology at PSCC-Q were eligible for the study. Families of these patients completed a questionnaire conducted by one interviewer. The Impact on Family Scale (IFS) questionnaire of Stein and Riessman was instituted. Patients were divided into two groups according to the cardiac diagnosis and the requirement for medical or surgical management. The first group included patients with CHD who do not need any medical or surgical intervention, .e.g. tiny VSD or small ASD. The second group included patients with complex CHD with single ventricle pathophysiology who underwent Glenn and/or Fontan procedures. The mean impact on family scores was compared among the different groups by two sample t test analysis. RESULTS: Families of 41 children with CHD were interrogated during the study period from September 2011 to February 2012. Patients were divided into two groups. Group one (20 patients, 49%) with simple CHD and group two (21 patients, 51%) with complex CHD who are managed in the univentricular tract. Families of children who underwent single ventricle repair had significantly higher IFS (mean and standard deviation of 62 [7]) than families with minor heart disease (mean of 51 [4]) (P=.005). CONCLUSION: Families of patients who underwent single ventricle repair have significant social impact because of their child illness. A supporting public group should be initiated and encouraged.
Keywords: article; child; clinical article; congenital heart disease; controlled study; cross-sectional study; emotion; Fontan procedure; Glenn shunt; heart atrium septum defect; heart single ventricle; heart ventricle septum defect; human; Impact on Family Scale; mitral valve disease; assessment of humans; priority journal; psychological aspect; pulmonary valve stenosis; social aspect

Living with half a heart--experiences of young adults with single ventricle physiology: a qualitative study. - Overgaard, D.; King, C.; Christensen, R.F.; Schrader, A.M.; Adamsen, L. (The Journal of cardiovascular nursing, 2013)
Approximately 3% of children with congenital heart disease born in Denmark have single ventricle physiology (SVP). In previous decades, these children did not survive into adulthood. However, because of new surgical techniques and improved medical care, they now have a 90% survival rate. Several studies have described the somatic status of SVP patients using clinical parameters; however, only a few studies have researched the life perspectives and coping skills in this patient group. The aim of this study was to investigate how young adults with an SVP diagnosis are coping with adulthood and the emotional experiences of daily life. Semistructured, qualitative interviews were held with 11 SVP respondents, selected by physical and psychological parameters identified in an earlier quantitative study. Data from the interviews were analyzed by a research group using a phenomenological methodology. The goal for SVP patients is to gain control over their disease to live normal lives. Patients require special support from their core network to overcome physical and psychological challenges. Respondents underscored the need for friends and resource persons outside the family to help lift them out of their role as disabled cardiac patients and provide them with "normal" life experiences.
Keywords: adaptive behavior; adolescent; adult; article; congenital malformation; daily life activity; Denmark; female; Fontan procedure; heart ventricle; human; male; middle aged; psychological aspect; quality of life; survivor

Full monosomy 21: Echocardiographic findings in the third molecularly confirmed case - Fisher, D.; Dipietro, A.; Murdison, K.A.; Lemieux, C.A. (Pediatric Cardiology, 2013)
Monosomy 21 is a rare chromosomal abnormality, with only nine cases reported in the literature. Affected infants display multiple dysmorphic features as well as skeletal, ocular, pulmonary, cardiac, renal, and genitourinary abnormalities. All monosomies are lethal except monosomy 21, but not all monosomy 21 fetuses survive to term. This report describes the echocardiographic findings and the congenital heart defects associated with the third case of molecularly confirmed full monosomy 21 in the literature. The cardiac defects included a mildly hypoplastic and hypertrophied left ventricle, a large ostium secundum atrial septal defect, a small anterior muscular ventricular septal defect, an interrupted inferior vena cava with azygos continuation, a parachute mitral valve, a bicuspid aortic valve, and a tortuous descending aorta. It also is the first description of a left pulmonary artery aneurysm and decreased left ventricular function as a component in the spectrum of defects found in full monosomy 21. © 2012 Springer Science+Business Media, LLC.
Keywords: carboplatin; cisplatin; docetaxel; fluorouracil; irinotecan; paclitaxel; adolescent; amniocentesis; amnion cell; arthrogryposis; article; bicuspid aortic valve; body dysmorphic disorder; breech presentation; cancer combination chemotherapy; cancer radiotherapy; cancer regression; cancer surgery; case report; cesarean section; cleft palate; clinodactyly; congenital hip dislocation; contracture; cryptorchism; cytogenetics; Doppler echocardiography; lack of drug effect; ear malformation; esophagojejunostomy; female; fetus; fetus echography; fluorescence in situ hybridization; genetic screening; heart atrium septum defect; heart left ventricle failure; heart ventricle hypertrophy; heart ventricle septum defect; human; hypoplastic left heart syndrome; infant; inferior cava vein obstruction; intrauterine growth retardation; karyotype; karyotype 45 xy; limb malformation; male; medical history; microcephaly; monosomy; monosomy 21; multimodality cancer therapy; pulmonary artery aneurysm; Roux Y anastomosis; stomach carcinoma; total stomach resection; treatment duration

Parenting under Pressure: A grounded theory of parenting young children with life-threatening congenital heart disease - Rempel, G.R.; Ravindran, V.; Rogers, L.G.; Magill-Evans, J. (Journal of Advanced Nursing, 2013)
Aim. To report a grounded theory study to describe the process of parenting young children who have survived hypoplastic left heart syndrome to inform parent-focused interventions. Background. Technological advances in paediatric cardiology worldwide have improved the survival rates for young children with hypoplastic left heart syndrome who undergo staged surgical palliation. These children, however, are at risk for life-threatening complications and parents are charged with the responsibility to monitor their children at home with minimal support and guidance from healthcare professionals once home. Design. A constructivist grounded theory study. Method. The study was conducted in 2006-2008. Participants were 25 parents (15 mothers, 10 fathers) and 28 grandparents (17 grandmothers, 11 grandfathers) of 15 young children (6months-4·5years) who had undergone the Sano surgical approach for hypoplastic left heart syndrome. The 53 interviews were digitally recorded, transcribed and analysed using open and focused coding, constant comparative analysis and memoing. Findings. A process of Parenting under Pressure emerged that was characterized by four overlapping and re-emerging phases: (1) realizing and adjusting to the inconceivable; (2) growing increasingly attached; (3) watching for and accommodating the unexpected; and (4) encountering new challenges. Conclusions. In-depth understanding of the phases of Parenting under Pressure provides direction for nurses to support parents of children who survive hypoplastic left heart syndrome. Interventions that help carers of children with complex health conditions move through the phases of our Parenting under Pressure process may help them safeguard the survival of their children, and their own survival as parents as they manage multiple demands. © 2012 Blackwell Publishing Ltd.
Keywords: adaptive behavior; adult; aged; article; caregiver; child parent relation; family; female; human; hypoplastic left heart syndrome; infant; male; mental stress; middle aged; parent; preschool child; psychological aspect; qualitative research

Neurobehavioral assessment of children presenting diverse congenital cardiopathologies - Porcayo-Mercado, M.R.; Otero-Ojeda, G.A.; Pliego-Rivero, F.B.; Aguirre-Pérez, D.M.; Ricardo-Garcell, J. (Journal of Clinical Psychology in Medical Settings, 2013)
Brain maturation in 1-36 month old children suffering from congenital cardiopathologies was assessed after a study of psychomotor development. The Rogers' test (Rogers et al., Developmental programming for infants and young children. Volume 2. Early intervention developmental profile, Revised edition, ESL/ELT Michigan, Ann Arbor, 1981) was applied to 65 children, of whom 21 presented with simple cardiopathologies (CpS) and 22 with complex cardiopathologies (CpC). All children were matched by age, sex and socioeconomic status to 22 healthy children in a control group (C). Mean differences between the three groups were established by applying the Kruskal-Wallis test, and mean differences between the C and CpS/CpC groups were determined using the Mann-Whitney test. The proportion of cases evaluated as "low" in each group was calculated by applying the Rogers' test, and a test of proportion differences was applied between the C and CpS/CpC groups. CpS children performed similarly to the C, whereas CpC children scored significantly lower than C children on all variables. It is highly likely that the suboptimal psychomotor performance observed in CpC children was due to compromised hemodynamics and related to subclinical immaturity of cerebral development. © 2012 Springer Science+Business Media, LLC.
Keywords: age; aortic coarctation; article; brain development; brain maturation; child; childhood disease; cognition; congenital cardiopathology; congenital heart disease; controlled study; emotion; Fallot tetralogy; female; heart atrium septum defect; heart hemodynamics; heart single ventricle; heart ventricle septum defect; human; hypothesis; immaturity; infant; Kruskal Wallis test; language; lung vein drainage anomaly; major clinical study; male; patent ductus arteriosus; perception; preschool child; priority journal; psychologist; psychometry; psychomotor development; psychomotor performance; rank sum test; self care; sex; social behavior; social status; tricuspid valve atresia

Monitoring of regional tissue oxygenation with near-infrared spectroscopy during the early postoperative course after superior cavopulmonary anastomosis - Hansen, J.H.; Schlangen, J.; Armbrust, S.; Jung, O.; Scheewe, J.; Kramer, H.-H. (European Journal of Cardio-thoracic Surgery, 2013)
OBJECTIVES: Near-infrared spectroscopy (NIRS) offers continuous non-invasive monitoring of regional tissue oxygenation. We evaluated NIRS monitoring during the postoperative course after superior cavopulmonary anastomosis in patients with hypoplastic left heart syndrome and anatomically related malformations. METHODS: Cerebral (cSO. 2) and somatic (sSO. 2) tissue oxygenations were recorded for 48 h and compared with routine measures of intensive care monitoring. Changes in parameters in the case of postoperative complications were evaluated. RESULTS: Data were obtained from 32 patients. Median age at operation was 2.9 (1.5-10.0) months and weight was 5.3 ± 1.0 kg. Postoperative complications occurred in 7 patients (pulmonary artery thrombus n = 4, pneumothorax n = 1, cardiopulmonary resuscitation n = 1 and low-cardiac output n = 1). cSO2 was 44 ± 14% at the end of the operation and reached its minimum of 40 ± 11% 2 h later (P = 0.018). Overall, cSO2 was depressed early after surgery and increased from a mean of 42 ± 11% during the first 4 postoperative hours to 57 ± 8% in the last 4 h of the study period (P < 0.001). The sSO2 decreased from 77 ± 11% during the early postoperative course to 68 ± 9% within the later course (P < 0.001). The cSO2 correlated with the arterial partial pressure of oxygen (pO2, r = 0.364, P < 0.001), with the arterial oxygen saturation (SaO2, r = 0.547, P < 0.001) and with the central venous oxygen saturation providing the strongest correlation (SvO2, r = 0.686, P < 0.001). Analysis of agreement between cSO2 and SvO2 measurements revealed a mean bias of 0.97 with limits of agreement between 19.8 and -17.9%. Inclusion of both cSO2 and sSO2 into a linear regression model slightly improved the prediction of SvO2 from NIRS values (r = 0.706, P < 0.001). The mean values of cSO2, sSO2, SaO2 and SvO2 during the early postoperative period were lower in patients with complications (cSO2: 45 ± 9 vs 29 ± 5%, P < 0.001; sSO2: 80 ± 11 vs 70 ± 6%, P = 0.004; SaO2: 76 ± 8 vs 66 ± 6%, P = 0.004; SvO2: 48 ± 14 vs 32 ± 6%, P < 0.001). CONCLUSIONS: NIRS technology allows inferring the global oxygenation from continuous non-invasive measurements of regional tissue oxygenation. The cSO. 2 is lowered in the early postoperative course. Lower cSO. 2 values in the early postoperative course may be predictive of postoperative complications. © The Author 2012. Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: arterial oxygen saturation; arterial oxygen tension; artery thrombosis; article; cavopulmonary connection; central venous pressure; clinical article; congenital heart malformation; correlation coefficient; heart hemodynamics; heart output; human; hypoplastic left heart syndrome; infant; intensive care unit; near infrared spectroscopy; non invasive measurement; oxygen saturation; pneumothorax; postoperative complication; postoperative period; priority journal; pulmonary artery; resuscitation; tissue oxygenation

Pulse oximetry home monitoring in infants with single-ventricle physiology and a surgical shunt as the only source of pulmonary blood flow - Öhman, A.; Strömvall-Larsson, E.; Nilsson, B.; Mellander, M. (Cardiology in the Young, 2013)
Background Shunt occlusion is a major cause of death in children with single ventricle. We evaluated whether one daily measurement of oxygen saturation at home could detect life-threatening shunt dysfunction. Methods A total of 28 infants were included. Parents were instructed to measure saturation once daily and if less than or equal to 70% repeat the measurement. Home monitoring was defined as positive when a patient was admitted to Queen Silvia Children's Hospital because of saturation less than or equal to 70% on repeated measurement at home. A shunt complication was defined as arterial desaturation and a narrowing of the shunt that resulted in an intervention to relieve the obstruction or in death. Parents' attitude towards the method was investigated using a questionnaire. Results A shunt complication occurred out of hospital eight times in eight patients. Home monitoring was positive in five out of eight patients. In two patients, home monitoring was probably life saving; in one of them, the shunt was replaced the same day and the other had an emergency balloon dilatation of the shunt. In three out of eight patients, home monitoring was negative; one had an earlier stage II and survived, but two died suddenly at home from thrombotic shunt occlusion. On seven occasions in three patients home monitoring was positive but there was no shunt complication. The method was well accepted by the parents according to the results of the questionnaire. Conclusion Home monitoring of oxygen saturation has the potential to detect some of the life-threatening shunt obstructions between stages I and II in infants with single-ventricle physiology. © Cambridge University Press 2012.
Keywords: acetylsalicylic acid; low molecular weight heparin; sotalol; warfarin; article; balloon dilatation; bradycardia; cardiopulmonary bypass; cause of death; child; clinical article; emergency surgery; heart arrhythmia; home monitoring; hospitalization; human; infant; lung blood flow; oxygen desaturation; oxygen saturation; patient attitude; pericardial effusion; postoperative complication; postoperative thrombosis; pulse oximetry; quality of life; questionnaire; sensitivity and specificity; surgical mortality; survival rate; thrombotic shunt occlusion

Head and neck vessel size by angiography predicts neo-aortic arch obstruction after norwood/sano operation for hypoplastic left heart syndrome - Seckeler, M.D.; Raucci, F.J.; Saunders, C.; Gangemi, J.J.; Peeler, B.B.; Anitha Jayakumar, K. (Journal of Invasive Cardiology, 2013)
Objectives: To identify and predict neo-aortic arch obstruction (NAAO) in children after Norwood/Sano operation (NO) for hypoplastic left heart syndrome (HLHS). Background: NAAO is associated with morbidity and mortality after NO for HLHS and no objective measure has predicted the initial occurrence of NAAO. Computational flow models of aortic coarctation demonstrate increased wall shear stress (WSS) in vessels proximal to the coarctation segment, which we believe also occurs with NAAO. These vessels respond by increasing their luminal diameter to maintain normal WSS. We hypothesized that the relative increase in diameters of head and neck vessels to the isthmus, as measured by angiography, would identify hemodynamically significant NAAO and predict future NAAO. Methods: Retrospective review of patients with HLHS and at least one catheterization with aortic angiography after NO. Diameters of head and neck vessels were totaled and divided by the isthmus diameter to give a head and neck index (HNI), which was compared to coarctation index (CI) for identifying and predicting future NAAO. Results: Forty-four patients were identified, 17 with and 27 without NAAO. Receiver operator characteristic analysis using a value for CI ≤0.5 showed a sensitivity of 47% and specificity of 89%. For HNI, a value >2.65 gave a sensitivity of 77% and specificity of 93%. Three patients who developed NAAO after their initial catheterization had CI >0.5, but abnormally high HNI >2.65. Conclusions: HNI is a more robust indicator of hemodynamically significant NAAO than CI and may predict its future occurrence after NO for HLHS.
Keywords: angiography; aortic arch; aortic coarctation; aortic occlusion; article; blood vessel diameter; clinical article; head; human; hypoplastic left heart syndrome; medical record review; neck; retrospective study; sensitivity and specificity; shear stress

Quality of life 4 years after complex heart surgery in infancy - Garcia Guerra, G.; Robertson, C.M.T.; Alton, G.Y.; Joffe, A.R.; Dinu, I.A.; Nicholas, D.; Ross, D.B.; Rebeyka, I.M. (Journal of Thoracic and Cardiovascular Surgery, 2013)
Objective: To determine the health-related quality of life at 4 years of age in children who had undergone cardiac surgery for congenital heart disease in early infancy. Methods: A prospective cohort study of infants undergoing cardiac surgery at 6 weeks of age or younger from July 2000 to June 2005 at the Stollery Children's Hospital. The quality of life was assessed using the Pediatric Quality of Life Inventory, version 4.0, generic core scales, and compared with normative values for the same age. The association between the perioperative variables and health-related quality of life was explored. Results: A total of 242 infants underwent complex heart surgery during the study period. Of the 166 eligible survivors, 130 were included. No significant differences were present between the children with single ventricle versus biventricular repairs, except for lower physical health summary scores in the single ventricle patients (P = .007). Compared with the normative data, the children with biventricular repair had lower total Pediatric Quality of Life Inventory, version 4.0, scores (P = .001) and psychosocial health summary scores (P < .001). The children with single ventricle repair also had lower physical health summary scores (P = .003). Older age at surgery and markers of postoperative low cardiac output syndrome were associated with worse health-related quality of life, and greater socioeconomic status was associated with better quality of life. Conclusions: At 4 years of age, health-related quality of life was significantly lower in children who had undergone surgery for congenital heart disease in early infancy. An association was found between age at surgery and postoperative low cardiac output and socioeconomic status and quality of life. Copyright © 2013 by The American Association for Thoracic Surgery.
Keywords: article; biventricular repair; cohort analysis; disease association; female; follow up; forward heart failure; heart output; heart surgery; human; infancy; infant; major clinical study; male; mental health; Pediatric Quality of Life Inventory version 4.0; perioperative period; postoperative period; priority journal; prospective study; quality of life; rating scale; single ventricle repair; Student t test

A predictive model for neurodevelopmental outcome after the norwood procedure - Mahle, W.T.; Lu, M.; Ohye, R.G.; William Gaynor, J.; Goldberg, C.S.; Sleeper, L.A.; Pemberton, V.L.; Mussatto, K.A.; Williams, I.A.; Sood, E.; Krawczeski, C.D.; Lewis, A.; et al. (Pediatric Cardiology, 2013)
Neurodevelopmental outcomes after the Norwood procedure for single right ventricular lesions are worse than those in the normal population. It would be valuable to identify which patients at the time of Norwood discharge are at greatest risk for neurodevelopmental impairment later in childhood. As such, this study sought to construct and validate a model to predict poor neurodevelopmental outcome using variables readily available to the clinician. Using data from the 14 month neurodevelopmental outcome of the Single-Ventricle Reconstruction (SVR) trial, a classification and regression tree (CART) analysis model was developed to predict severe neurodevelopmental impairment, defined as a Psychomotor Development Index (PDI) score lower than 70 on the Bayley Scales of Infant Development-II. The model then was validated using data from subjects enrolled in the Infant Single Ventricle (ISV) trial. The PDI scores were lower than 70 for 138 (44 %) of 313 subjects. Predictors of a PDI lower than 70 were post-Norwood intensive care unit (ICU) stay longer than 46 days, genetic syndrome or other anomalies, birth weight less than 2.7 kg, additional cardiac surgical procedures, and use of five or more medications at hospital discharge. Using these risk factors, the CART model correctly identified 75 % of SVR subjects with a PDI lower than 70. When the CART model was applied to 70 subjects from the ISV trial, the correct classification rate was 67 %. This model of variables from the Norwood hospitalization can help to identify infants at risk for neurodevelopmental impairment. However, given the overall high prevalence of neurodevelopmental impairment and the fact that nearly one third of severely affected children would not have been identified by these risk factors, close surveillance and assessment for early intervention services are warranted for all infants after the Norwood procedure. © 2012 Springer Science+Business Media, LLC.
Keywords: article; child; cognition; cognitive defect; female; genetic disorder; human; infant; intensive care unit; low birth weight; major clinical study; male; Norwood procedure; patient monitoring; postoperative period; preschool child; risk factor

Increased extracorporeal membrane oxygenation center case volume is associated with improved extracorporeal membrane oxygenation survival among pediatric patients - Karamlou, T.; Vafaeezadeh, M.; Parrish, A.M.; Cohen, G.A.; Welke, K.F.; Permut, L.; McMullan, D.M. (Journal of Thoracic and Cardiovascular Surgery, 2013)
Objective: We sought to examine the relationship between extracorporeal membrane oxygenation center case volume and survival in pediatric patients requiring extracorporeal membrane oxygenation support. Methods: Pediatric patients (≤20 years) undergoing extracorporeal membrane oxygenation cannulation were identified using the Healthcare Cost and Utilization Project Kids' Inpatient Database for 2000 to 2009. Annual hospital extracorporeal membrane oxygenation volume tertiles were <15 patients/year (low volume), 15 to 30 patients/year (medium volume), and >30 patients/year (high volume). Cases of extracorporeal membrane oxygenation were segregated by indication into cardiac and noncardiac groups. Cases of cardiac extracorporeal membrane oxygenation were mapped to Risk Adjustment for Congenital Heart Surgery categories to adjust for case complexity. Weighted multivariable logistic and linear regression models identified determinants of in-hospital mortality. Results: Overall, 3867 cases of extracorporeal membrane oxygenation were identified, yielding a national estimate of 6333 ± 495 cases. Extracorporeal membrane oxygenation was used with nearly equivalent prevalence across volume tertiles for all Risk Adjustment for Congenital Heart Surgery categories, suggesting that patient selection for extracorporeal membrane oxygenation was fairly uniform. A higher annual extracorporeal membrane oxygenation volume tertile was associated with reduced in-hospital mortality (P = .01) within nearly all Risk Adjustment for Congenital Heart Surgery categories. After adjustment for Risk Adjustment for Congenital Heart Surgery category and other patient variables, lower extracorporeal membrane oxygenation volume remained an important determinant of in-hospital death (odds ratio, 1.75; 95% confidence interval, 1.03-2.94; P = .03). Conclusions: Higher extracorporeal membrane oxygenation case volume is associated with improved hospital survival in pediatric cardiac extracorporeal membrane oxygenation patients. The results of this study may support the paradigm of regionalized centers of excellence for managing pediatric cardiac extracorporeal membrane oxygenation patients. Copyright © 2013 by The American Association for Thoracic Surgery.
Keywords: oxygen; article; atrioventricular septal defect; cannulation; child; data base; extracorporeal oxygenation; female; hospital patient; human; hypoplastic left heart syndrome; major clinical study; male; mortality; oxygen supply; pediatrics; preschool child; prevalence; priority journal; risk reduction; survival; workload

Two-stage biventricular rehabilitation for critical aortic stenosis with severe left ventricular dysfunction. - Hammel, J.M.; Duncan, K.F.; Danford, D.A.; Kutty, S. (European journal of cardio-thoracic surgery : official journal of the European Association for Cardio-thoracic Surgery, 2013)
Critical aortic valve stenosis (CAS) in the newborn is treated by balloon or surgical aortic valve intervention with nearly equal success, but the subset of patients with severe left ventricular (LV) dilation and dysfunction present a significant mortality risk. We describe a two-stage surgical management approach for those infants who represent an unusually high failure risk for either aortic valvotomy or conventional stage 1 single ventricle (Norwood) palliation because of severe LV dysfunction at the time of presentation. A two-stage surgical palliation was undertaken consisting of surgical aortic valvotomy, bilateral pulmonary artery banding and atrial septectomy (stage 1), followed by patch closure of the atrial septal defect, ligation of the ductus arteriosus and removal of the pulmonary artery bands (stage 2) with prostaglandin infusion continued between stages to maintain right ventricular contribution to systemic perfusion via the ductus arteriosus. Four neonates with CAS and severely depressed LV systolic function were treated using this strategy. LV dilation resolved and systolic function improved in three patients after 2, 2 and 4 weeks, enabling stage 2. LV dysfunction did not improve in one patient who expired before conversion to biventricular circulation. Of the three who proceeded to stage 2, one infant continued to have poor biventricular diastolic function that precluded conversion, and this patient also died. The remaining two infants are now alive and well at 34 and 44 months of age. These two had the most severe LV dilation (internal dimension Z-scores of 6.9 and 7.7) and the worst systolic function (fractional shortening 4 and 10%) at presentation, and both were born prematurely (32 and 35 weeks). A two-stage surgical approach may improve the likelihood of survival in selected patients with CAS presenting with severely depressed LV systolic function. Relief of LV distention may have contributed to the improvement of LV function in these infants.
Keywords: aortic valve; aortic valve stenosis; article; heart left ventricle function; heart surgery; human; infant; methodology; newborn; pathophysiology; physiology; pulmonary artery; retrospective study

Capture of complexity of specialty care in pediatric cardiology by work RVU measures - Bergersen, L.; Gauvreau, K.; McElhinney, D.; Fenwick, S.; Kirshner, D.; Harding, J.; Hickey, P.; Mayer, J.; Marshall, A. (Pediatrics, 2013)
OBJECTIVE: We sought to determine the relationship between relative value units (RVUs) and intended measures of work in catheterization for congenital heart disease. METHODS: RVU was determined by matching RVU values to Current Procedural Terminology codes generated for cases performed at a single institution. Differences in median case duration, radiation exposure, adverse events, and RVU values by risk category and cases were assessed. Interventional case types were ranked from lowest to highest median RVU value, and correlations with case duration, radiation dose, and a cases-predicted probability of an adverse event were quantified with the Spearman rank correlation coefficient. RESULTS: Between January 2008 and December 2010, 3557 of 4011 cases were identified with an RVU and risk category designation, of which 2982 were assigned a case type. Median RVU values, radiation dose, and case duration increased with procedure risk category. Although all diagnostic cases had similar RVU values (median 10), adverse event rates ranged from 6% to 21% by age group (P , .001). Median RVU values ranged from 9 to 54 with the lowest in diagnostic and biopsy cases and increasing with isolated and then multiple interventions. Among interventional cases, no correlation existed between ranked RVU value and case duration, radiation dose, or adverse event probability (P = .13, P = .62, and P = .43, respectively). CONCLUSIONS: Time, skill, and stress inherent to performing catheterization procedures for congenital heart disease are not captured by measurement of RVU alone. Copyright © 2013 by the American Academy of Pediatrics.
Keywords: adolescent; adult; analytic method; angiography; article; child; congenital heart disease; correlation analysis; correlation coefficient; Current Procedural Terminology; data base; disease severity; female; fluoroscopy; Fontan procedure; health care financing; health care personnel; heart atrium septum defect; heart catheterization; heart muscle biopsy; heart transplantation; hemodynamics; human; human tissue; infant; intervention study; major clinical study; male; nomenclature; patent ductus arteriosus; percutaneous transluminal angioplasty; preschool child; priority journal; probability; prospective study; radiation dose; reimbursement; relative value unit system; school child; stent; validity

Ethics and Clinical Trials in Congenital Heart Disease - Shaddy, R.E. (World Journal for Pediatric and Congenital Heart Surgery, 2013)
There is a strong need for well-designed clinical trials in congenital heart disease. Research in children, including children with congenital heart disease, must adhere to the highest ethical standards at all times. © The Author(s) 2012.
Keywords: placebo; sildenafil; tadalafil; article; beneficence; child health care; clinical trial (topic); congenital heart disease; exercise; Fontan procedure; human; justice; medical ethics; medical research; patient autonomy; phase 1 clinical trial (topic); phase 2 clinical trial (topic); phase 3 clinical trial (topic); practice guideline; priority journal; randomized controlled trial (topic); total quality management

The 24th annual ASE scientific sessions - The pediatric & congenital heart disease program is a "can't miss" event for 2013! - Eidem, B.; Mertens, L. (Journal of the American Society of Echocardiography, 2013)
Keywords: childhood disease; clinical assessment; clinical assessment tool; clinical decision making; congenital heart disease; diastolic dysfunction; health program; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; human; hypoplastic left heart syndrome; interpersonal communication; life event; lung circulation; palliative therapy; pathologist; protein losing gastroenteropathy; short survey; surgeon; three dimensional echocardiography

Bilateral branch pulmonary artery banding as a bridge to decision/ preoperative optimization of high-risk neonates with hypoplastic left heart syndrome - Kurkluoglu, M.; Jonas, R.A.; Sinha, P. (World Journal for Pediatric and Congenital Heart Surgery, 2013)
We present our experience with bilateral branch pulmonary artery banding as a bridge to decision/optimization of hemodynamics, followed by standard Norwood stage I palliation in very high-risk infants with hypoplastic left heart syndrome. © The Author(s) 2012.
Keywords: angioplasty; article; bilateral branch pulmonary artery banding; blalock hanlon operation; cardiovascular stent; cardiovascular surgery; case report; clinical decision making; clinical feature; congestive heart failure; extracorporeal oxygenation; female; high risk patient; human; hypoplastic left heart syndrome; infant; lung artery banding; male; Norwood procedure; priority journal; resuscitation; risk reduction; treatment outcome

Infant cardiac surgery: Mothers tell their story: A therapeutic experience - Re, J.; Dean, S.; Menahem, S. (World Journal for Pediatric and Congenital Heart Surgery, 2013)
Background: Serious congenital heart disease frequently requires major congenital heart surgery. It causes much distress for parents, which may not always be recognized and treated appropriately. Patients and Methods: As part of a larger study, 26 mothers of two-month-old infants subjected to recent cardiac surgery were interviewed in depth. Each mother was invited to describe her own and what she perceived were her infant's experiences and to comment on the interview process. A systematic content analysis of the interviews was performed using qualitative research methodology. Results: Almost all participants described acute stress symptoms relating to the diagnosis and the infant's surgery. In addition, most mothers reported that the interview helped them to think about and integrate what had happened to them and their infant, suggesting a probable therapeutic value to the interview. Conclusions: A suitably qualified and experienced mental health professional, assisting the mother to tell her story about the diagnosis and her infant's cardiac surgery, may provide a valuable, brief, and very cost-effective therapeutic intervention for these mothers and infants. It has the potential to alleviate maternal distress, with associated gains for the developing mother-infant relationship, reducing infant morbidity, and enhancing the quality of life for both infant and mother. © The Author(s) 2013.
Keywords: acute stress; altruism; anticipatory anxiety; article; child care; congenital heart disease; content analysis; coping behavior; cost effectiveness analysis; female; heart surgery; heart ventricle septum defect; helplessness; human; hypoplastic left heart syndrome; infant; infant mortality; intensive care unit; interview; maternal stress; mental dissociation; morbidity; mother child relation; personal experience; posttraumatic stress disorder; priority journal; qualitative analysis; qualitative research; quality of life; self report; separation anxiety; social participation; treatment outcome

Health-related quality of life and congenital heart disease in Australia - Eagleson, K.J.; Justo, R.N.; Ware, R.S.; Johnson, S.G.; Boyle, F.M. (Journal of Paediatrics and Child Health, 2013)
Aim To determine whether, in children with congenital heart disease (CHD), disease severity is associated with health-related quality of life (HRQOL) and impact on the family. Methods Cross-sectional, single-centre study comparing HRQOL outcomes of age and sex matched children with hypoplasia of the left ventricle (HLV) (n = 31) and tetralogy of Fallot (n = 29) was performed in Queensland, Australia. HRQOL was assessed using generic and disease-specific components of the Paediatric Quality of Life Inventory Measurement Model (PedsQL). Intra-diagnostic age group comparisons of HRQOL were examined. Impact of CHD on families and parental HRQOL was assessed using the PedsQL Family Impact Scale. Results Child and parent-proxy reporting indicate children with HLV have significantly lower overall HRQOL than children with tetralogy of Fallot across generic domains of HRQOL (P < 0.0001), with significantly lower scores in physical (P < 0.0001) and psychosocial (P < 0.0001) health domains. No significant difference in child reporting across domains of the Cardiac Module is evident. Parent-proxy reporting indicates significantly lower scores on the symptom scales for children with HLV (P < 0.001), with greater cognitive problems (P < 0.02) and perceived treatment anxiety (P < 0.01). No significant differences in HRQOL were identified between age groups. HLV has a greater overall family impact, with significantly lower parental HRQOL (P = 0.0001) and family functioning (P < 0.0001) summary scores. Conclusions The more severe condition of HLV is associated with poorer HRQOL in some domains and has greater impact on parental HRQOL and family functioning. © 2013 The Authors. Journal of Paediatrics and Child Health.
Keywords: adolescent; adult; article; Australia; child; child parent relation; disease severity; Fallot tetralogy; family functioning; female; human; hypoplastic left heart syndrome; major clinical study; male; parent; patient participation; PedsQL Family Impact Scale; preschool child; priority journal; prognosis; quality of life; rating scale; school child

Genetic Testing in Congenital Heart Disease: Ethical Considerations - Lin, K.Y.; D’Alessandro, L.C.A.; Goldmuntz, E. (World Journal for Pediatric and Congenital Heart Surgery, 2013)
On March 16, 2012, the Ethics of the Heart 2012: Ethical and Policy Challenges in Pediatric and Adult Congenital Heart Disease Conference took place in Philadelphia, Pennsylvania. The first session focused on the ethics surrounding genetic testing in patients with congenital heart disease. Summarized here is the introductory presentation given by Dr Elizabeth Goldmuntz entitled “The Role of Genetic Testing in Congenital Heart Disease,” followed by a case presentation given by Dr Lisa D’Alessandro. The case and the panel discussion that ensued highlight several ethical principles and challenges in this unique patient population.
Keywords: act; article; chromosome deletion 22q11; congenital heart disease; ethics; fluorescence in situ hybridization; gastroesophageal reflux; gene mutation; genetic screening; genetic variability; genotype; health insurance; hospitalization; human; hypoplastic left heart syndrome; intensive care unit; multiplex ligation dependent probe amplification; nuclear magnetic resonance imaging; priority journal; recurrent disease; survival; velocardiofacial syndrome

Infant Cardiac Surgery: Mothers Tell Their Story: A Therapeutic Experience - Re, J.; Dean, S.; Menahem, S. (World Journal for Pediatric and Congenital Heart Surgery, 2013)
Background: Serious congenital heart disease frequently requires major congenital heart surgery. It causes much distress for parents, which may not always be recognized and treated appropriately. Patients and Methods: As part of a larger study, 26 mothers of two-month-old infants subjected to recent cardiac surgery were interviewed in depth. Each mother was invited to describe her own and what she perceived were her infant’s experiences and to comment on the interview process. A systematic content analysis of the interviews was performed using qualitative research methodology. Results: Almost all participants described acute stress symptoms relating to the diagnosis and the infant’s surgery. In addition, most mothers reported that the interview helped them to think about and integrate what had happened to them and their infant, suggesting a probable therapeutic value to the interview. Conclusions: A suitably qualified and experienced mental health professional, assisting the mother to tell her story about the diagnosis and her infant’s cardiac surgery, may provide a valuable, brief, and very cost-effective therapeutic intervention for these mothers and infants. It has the potential to alleviate maternal distress, with associated gains for the developing mother–infant relationship, reducing infant morbidity, and enhancing the quality of life for both infant and mother.
Keywords: adolescent; adult; altruism; anticipatory anxiety; article; congenital heart disease; content analysis; female; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; infant; intensive care unit; mother child relation; posttraumatic stress disorder; priority journal; qualitative research; quality of life; resuscitation; semi structured interview; treatment outcome

Neurodevelopmental burden at age 5 years in patients with univentricular heart - Sarajuuri, A.; Jokinen, E.; Mildh, L.; Tujulin, A.-M.; Mattila, I.; Valanne, L.; Lönnqvist, T. (Pediatrics, 2012)
BACKGROUND: Despite increasing survival, patients with hypoplastic left heart syndrome (HLHS) and other forms of functionally univentricular heart defects (UVHs) remain at increased risk of long-term neurodevelopmental deficits. METHODS: A nationwide sample of 23 patients with HLHS, 13 with UVH, and 40 controls were followed prospectively until the age of 5 years, when neurologic, neuropsychological, and motor examinations and brain MRI were performed. RESULTS: The median full-scale IQ was significantly lower in patients with HLHS (97, P < .001) and patients with UVH (112, P = .024) compared with controls (121). Major neurodevelopmental impairment was found in 26% of the patients with HLHS and 23% of those with UVH, and minor neurologic dysfunction was found in 43% and 46%, respectively. MRI revealed abnormalities, mostly ischemic changes of different degrees, in 82% of the patients with HLHS and in 56% of those with UVH. Prominent changes were significantly associated with neurodevelopmental findings and parental reports of adaptive behavior. In linear regression, significant risk factors for a worse outcome were a history of clinical seizures in connection with the primary operation, a lower diameter of the neonatal ascending aorta, and several pre-, peri-, and postoperative factors related to the primary and bidirectional Glenn operations. CONCLUSIONS: Although median cognitive performance was within the normal range, neurodevelopmental and brain MRI abnormalities were found in the majority of the patients with UVH, and especially in those with HLHS, at preschool age. Both a narrowed ascending aorta and operation-related factors contributed to these findings. Copyright © 2012 by the American Academy of Pediatrics.
Keywords: adaptive behavior; article; ascending aorta; child; clinical article; controlled study; developmental disorder; disease severity; Glenn shunt; heart muscle ischemia; heart single ventricle; heart surgery; human; hypoplastic left heart syndrome; intelligence quotient; motor performance; nervous system development; neurologic disease; neurologic examination; neuropsychological test; nuclear magnetic resonance imaging; perioperative period; postoperative period; preoperative period; priority journal; prospective study; risk factor; seizure; surgical technique

Prevalence of ADHD symptoms in patients with congenital heart disease - Hansen, E.; Poole, T.A.; Nguyen, V.; Lerner, M.; Wigal, T.; Shannon, K.; Wigal, S.B.; Batra, A.S. (Pediatrics International, 2012)
Objective: The presence of attention-deficit-hyperactivity disorder (ADHD) symptoms in children with congenital heart disease (CHD) was investigated. Methods: Swanson, Nolan and Pelham teacher and parent rating scales, version 4 (SNAP-IV), commonly used for assessing symptoms of ADHD, were completed by parents and counselors of children who attended a CHD summer camp. Mean scores (n = 51) were compared with two comparison groups without CHD: patients with ADHD (n = 75) and patients without ADHD (n = 41). Parent scores were also compared to previously published parent normative data. Results: Patients with CHD were reported to have elevated SNAP-IV scores by parents and counselors (11.8%). Parent ratings of inattention were significantly greater in CHD subjects when compared to the comparison group without ADHD (P < 0.001), and similar to the ADHD-positive comparison group. Regarding parent ratings of hyperactivity and impulsivity, the CHD group was significantly lower than the ADHD-positive controls (P = 0.024) but greater than the ADHD-negative controls (P < 0.001). Conclusion: ADHD symptoms are more prevalent in children with CHD. Parent ratings of inattention and hyperactivity symptoms in CHD patients are similar to ratings in children diagnosed with ADHD. There is a trend towards a greater prevalence of inattention symptoms in patients with cyanosis or single ventricle physiology. © 2012 The Authors.
Keywords: adolescent; article; attention deficit disorder; child; congenital heart disease; controlled study; cyanosis; female; human; hyperactivity; impulsiveness; major clinical study; male; parent; prevalence; priority journal; rating scale; school child; Swanson, Nolan and Pelham teacher and parent rating scale IV

Hemodynamic simulation for surgical treatment of congenital heart disease. - Qian, Y.; Liu, J.L.; Liu, J.F. (Conference proceedings : ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Conference, 2012)
Numerical analysis of cardiovascular flow is one of several methods of use for the quantitative evaluation of patient-specific treatments. However, due to the complexity of vascular geometry and flow conditions, the cardiovascular flow simulation continues to be a challenging project. As the flow at the peak of systolic heart beat displayed full turbulence, the congenital heart treatments, Norwood and TCPC procedure, were investigated through the use of computational hemodynamic technology, in the present study. On the other hand, at diastolic period, the flow fell to an almost sedentary state. This indicated that the cardiovascular flow experienced a strange transition of flow from systolic peak to diastole. Thus, in order to accurately simulate this transitional flow, a very small time step was applied in the k - ε turbulent model calculation. Energy losses (EL), local pressure and wall shear stress were analyzed to estimate the result of clinical treatments. It was found that the value of EL, including the influence of respiration, was 1.5 times higher than the value of EL, disregarding respiratory influences. These results indicated that the hemodynamic outcomes of TCPC treatment are noticeably influenced by respiration. The effect of respiration plays an important role in estimating the results of TCPC treatment and thus should be included as one of the important conditions of computational hemodynamic analysis.
Keywords: article; biological model; computer assisted surgery; computer simulation; coronary artery blood flow; Fontan procedure; hemodynamics; human; hypoplastic left heart syndrome; infant; newborn; Norwood procedure; pathology; pathophysiology; statistics; three-dimensional imaging

Prenatal diagnosis of hypoplastic left heart syndrome: Impact of counseling patterns on parental perceptions and decisions regarding termination of pregnancy - Hilton-Kamm, D.; Chang, R.-K.; Sklansky, M. (Pediatric Cardiology, 2012)
An online survey for parents of children with congenital heart disease (CHD) was developed to study parents' experiences at the time of diagnosis. The survey was distributed to online support groups. A total of 841 responses from parents of children with CHD were received during a 4-week period. The current study examined those respondents (211 [25 %]) who reported their child's diagnosis as hypoplastic left heart syndrome (HLHS). Among these, 138 (65 %) reported receiving the diagnosis prenatally. 32 % of those receiving a prenatal diagnosis reported that after they declined to terminate the pregnancy, termination was mentioned again by their physicians. Parents who had termination mentioned again after their initial decline reported significantly lower optimism regarding their child's life expectancy than those who did not have it mentioned again (66 vs. 94 %, p < 0.001); were more likely to interpret the term "rare" to mean "little or no chance of survival" (34 vs. 13 %, p = 0.01); and were more likely to change pediatric cardiologists (PCs) (43 vs. 12 %, p < 0.001). Similarly, 22 % of respondents receiving a prenatal diagnosis reported feeling pressure to terminate the pregnancy by the PC. Those who felt pressure to terminate reported lower optimism about their child's life expectancy than respondents who did not feel pressure (48 vs. 88 %, p < 0.001) and were more likely to choose a new PC (48 vs. 17 %, p < 0.001). In our cohort of parents, when termination of pregnancy was mentioned after the parents declined it, or if the parents felt pressure to terminate, the parents perceived a lower chance of survival, felt less optimistic about their child's life expectancy, and were more likely to choose another PC for long-term follow-up care. Our study could not determine whether repeated discussions of the possibility for termination of pregnancy independently impacts parental optimism regarding prognosis or whether those who counsel with repeated discussions of termination tend to have more guarded notions of the prognosis of children with HLHS. Further study is warranted to identify the implications of counseling patterns on parental perceptions and decisions regarding termination of pregnancy. © 2012 Springer Science+Business Media, LLC.
Keywords: adult; article; cardiologist; empathy; family decision making; female; human; hypoplastic left heart syndrome; life expectancy; major clinical study; male; optimism; parent counseling; parental attitude; perception; pregnancy termination; prenatal diagnosis; prognosis; support group

Quality of life, health status, and depression: comparison between adolescents and adults after the Fontan procedure with healthy counterparts. - Pike, N.A.; Evangelista, L.S.; Doering, L.V.; Eastwood, J.A.; Lewis, A.B.; Child, J.S. (The Journal of cardiovascular nursing, 2012)
Quality of life (QOL) in adolescents and adults who have undergone the Fontan procedure and are living with only 1 ventricle is presumed to be diminished. This study aimed to compare QOL, health status, and prevalence of depression in adolescents/adults after the Fontan procedure with healthy counterparts and to identify predictors of QOL in the Fontan group. Using a comparative, cross-sectional design, 54 adolescents and adults with single ventricle congenital heart disease who have undergone the Fontan procedure were compared with 66 age-matched healthy counterparts. Quality of life, health status, depression, and social support were measured using the Satisfaction With Life Scale, Short Form Survey Version 2, Patient Health Questionnaire Depression Module, and Multidimensional Scale of Perceived Social Support. Clinical variables were abstracted from medical records. Predictors of QOL were determined using multiple linear regression. Adolescents and adults in the Fontan group reported lower physical health status (mean [SD] = 46.5 [9.3] vs mean [SD] = 55.9 [5.1], P < .001) and were more depressed (mean [SD] = 7.3 [5.9] vs mean [SD] = 4.5 [4.3], P < .004) than their healthy counterparts. There were no differences in QOL, mental health status, or social support between the 2 groups. Functional status (New York Heart Association class), depression, and social support accounted for 55% of the variance in QOL in the Fontan group. Despite lower levels of physical health, the QOL of Fontan patients was comparable with that of their healthy counterparts; this finding contradicts previous proxy reports, self-reports, and assumptions that QOL is lower in patients with complex single ventricle congenital heart disease. However, because Fontan patients were more depressed than their healthy counterparts, the need for early screening and detection is warranted.
Keywords: adolescent; adult; article; comparative study; cross-sectional study; depression; female; Fontan procedure; health status; human; male; quality of life; questionnaire; retrospective study

The implementation of neonatal peritoneal dialysis in a clinical setting - Unal, S.; Bilgin, L.; Gunduz, M.; Uncu, N.; Azili, M.N.; Tiryaki, T. (Journal of Maternal-Fetal and Neonatal Medicine, 2012)
Objective: To investigate etiology, outcome and complications related to neonatal peritoneal dialysis (PD). Methods: Neonates treated with PD in our neonatal intensive care unit during 20072010 were analyzed retrospectively. Results: Among 4036 hospitalized neonates; 20 neonates (0.5%) who underwent 21 cycles of PD [7 preterm, 13 term; 13 female, 7 male] were included. The mean birth weight was 2930.2 ± 720.6 g (11204570), mean gestational age was 37.5 ± 3.5 weeks (2741). The etiologic disorders included inborn errors of metabolism (propionic acidemia, methylmalonic acidemia, citrullinemia, glutaric aciduria type2, maple syrup urine disease, 10), or acute renal failure secondary to perinatal asphyxia (4), sepsis (2), prematurity (2), hypoplastic left heart syndrome (1), kernicterus (1). The complications included peritonitis (2), early leakage (4), hemorrhage (1), catheter removal (3) and occlusion (2). The mortality rate was 50%. The gestational ages and birth weights of surviving neonates were higher (p < 0.05). Among surviving neonates, chronic renal failure (1), severe (4) and moderate neuromotor impairment (2) developed within 443 months. Conclusion: PD, although invasive, is an effective therapy in neonates. The complexity and invasiveness of the procedure is probably responsible for high rate of complications and mortality. If appropriate catheter selection and technique in the placement should be done, PD might improve outcome. © 2012 Informa UK, Ltd.
Keywords: acute kidney failure; article; birth weight; bleeding; catheter occlusion; catheter removal; child hospitalization; chronic kidney failure; citrullinemia; clinical article; clinical practice; disease severity; female; gestational age; human; hypoplastic left heart syndrome; inborn error of metabolism; kernicterus; male; maple syrup urine disease; methylmalonic acidemia; motor dysfunction; multiple acyl CoA dehydrogenase deficiency; newborn; newborn care; newborn intensive care; newborn morbidity; newborn mortality; outcome assessment; perinatal asphyxia; peritoneal dialysis; peritonitis; prematurity; priority journal; propionic acidemia; retrospective study; sepsis

Health care professionals' attitudes about pregnancy termination for different fetal anomalies - Janvier, A.; Couture, E.; Deschenes, M.; Nadeau, S.; Barrington, K.; Lantos, J. (Paediatrics and Child Health (Canada), 2012)
BACKGROUND: Health care professionals (HCPs) may be involved in counselling women after an antenatal diagnosis of various fetal anomalies. Many pregnant women consider termination of pregnancy (TOP) after antenatal diagnosis of various fetal anomalies. Little is known, however, about the attitudes of HCPs regarding TOP for specific antenatal diagnoses. OBJECTIVE: To determine the attitudes and opinions of HCPs in maternal and child health regarding TOP for fetal anomalies of varying severity. METHODS: An anonymous questionnaire was distributed to four groups of HCPs: obstetric residents; paediatric residents; delivery room nurses; and neonatal intensive care nurses. Respondents were asked about TOP if they or their spouse were to receive an antenatal diagnosis for five prenatally diagnosed conditions: trisomy 21; trisomy 18; cleft lip and palate; Turner syndrome; and hypoplastic left heart syndrome. RESULTS: Two hundred eighty HCPs answered the questionnaire (90% response rate). Ten per cent of respondents would not consider TOP under any of the circumstances described. Among those who would consider TOP, they were most likely to do so for trisomy 18 and least likely for cleft lip and palate, and fairly evenly divided among the remaining three conditions (hypoplastic left heart syndrome [65%], trisomy 21 [56%] and Turner syndrome [37%]). Paediatric residents were less likely to choose TOP than other groups and obstetrics residents were most likely. CONCLUSIONS: Attitudes of HCPs toward TOP vary according to prenatally identified condition and professional group. More rigorous analysis should be performed regarding the process of counselling and the impact of HCPs beliefs on parental decisions. ©2012 Pulsus Group Inc. All rights reserved.
Keywords: adult; article; child health; cleft lip palate; disease severity; female; fetus; fetus malformation; health personnel attitude; human; hypoplastic left heart syndrome; male; maternal welfare; medical decision making; nurse attitude; parent counseling; parenthood; pediatrician; physician attitude; pregnancy termination; prenatal diagnosis; questionnaire; religion; resident; trisomy 18; trisomy 21; Turner syndrome

Pain management after surgery for single-ventricle palliation using the hybrid approach - Naguib, A.N.; Dewhirst, E.; Winch, P.D.; Simsic, J.; Galantowicz, M.; Tobias, J.D. (Pediatric Cardiology, 2012)
The hybrid pathway for the management of patients with hypoplastic left heart syndrome was pioneered at our institution and is the preferred approach compared with the traditional Norwood pathway. Patients undergoing this surgery are generally \6 months of age, and pain management in this age group after surgery for complex congenital heart disease (CHD) may be particularly challenging. We retrospectively reviewed our painmanagement strategy after stage 1 hybrid procedure (HS1) and evaluated its efficacy, especially in the setting of early tracheal extubation. We retrospectively reviewed the records of patients receiving fentanyl analgesia after HS1 palliation for single-ventricle anatomy between June 2008 and August 2011. In addition to demographic data, we also recorded the mode of analgesia, total fentanyl administered during the first 48 postoperative hours, and total hours of fentanyl use. Other data collected included pain scores, adverse effects, time of tracheal extubation, and use of adjunctive medications, such as dexmedetomidine. Nursecontrolled analgesia (NCA) with fentanyl was used in 21 of the 33 patients in the study cohort, with the remainder receiving a continuous fentanyl infusion. NCA-fentanyl was the method of choice in 12 of the 13 patients whose tracheas were extubated in the operating room versus 9 of 20 patients who received postoperative mechanical ventilation and tracheal intubation (p = 0.0093). During the first and second 24 h after surgery, fentanyl requirements were lower in patients whose tracheas were extubated (11.8 ± 7.6 vs. 20.6 ± 18.1 and 6.6 ± 10.3 vs. 24.3 ± 20.4 lg/kg, respectively). Adverse effects were noted in 3 of the 33 patients (9%) and included one episode each of respiratory depression requiring reintubation of the trachea, pruritus, and excessive sedation. Dexmedetomidine was used as an adjunct medication in 5 patients and resulted in decreased fentanyl use (6.3 ± 1.3 vs. 19 ± 15.9 lg/kg in the first 24 postoperative hours and 7.9 ± 3.5 vs. 19 ± 20.3 lg/kg in the second 24 postoperative hours). Fentanyl administered by way of continuous infusion or NCA provided effective postoperative analgesia with a limited adverse effect profile after HS1 surgery in neonates with complex CHD. Fentanyl requirements were lower in patients who achieved early tracheal extubation as well as those who received dexmedetomidine. © Springer Science+Business Media, LLC 2012.
Keywords: dexmedetomidine; fentanyl; analgesia; article; artificial ventilation; clinical article; clinical effectiveness; cohort analysis; continuous infusion; demography; endotracheal intubation; extubation; female; heart single ventricle; heart surgery; human; hypoplastic left heart syndrome; infant; male; newborn; nurse controlled analgesia; postoperative analgesia; postoperative pain; postoperative period; pruritus; respiration depression; retrospective study; sedation; side effect; stage 1 hybrid procedure; therapy effect

Physician counseling, informed consent and parental decision making for infants with hypoplastic left-heart syndrome - Paris, J.J.; Moore, M.P.; Schreiber, M.D. (Journal of Perinatology, 2012)
Until the development in 1980 by William Norwood of a staged palliative surgical procedure for hypoplastic left heart syndrome (HPLHS), there was no treatment for that condition. With medical developments in the 1980s, parents had the option of the Norwood procedure, transplantation or comfort care for a child born with HPLHS. With an improvement in the survival rate for the Norwood procedure from an initial 30% to now better than 80%, some physicians believe that comfort care should no longer be an option. If, however, medically sophisticated parents, who know the neurological and motor skills impairments that accompany HPLHS, object to the surgery, they are allowed to opt for comfort care. This two-pronged approach to medical treatment seems to violate the norms on equity and fairness in the care of the patient. Parents need to be informed about long-term neurological and motor skill development as well as survival rates to give informed consent. © 2012 Nature America, Inc. All rights reserved.
Keywords: article; cardiopulmonary bypass; child care; childhood mortality; counseling; decision making; health care quality; heart transplantation; human; hypoplastic left heart syndrome; infant; informed consent; morbidity; motor performance; Norwood procedure; outcome assessment; parental decision making; physician counseling; quality of life; survival rate

Common carotid artery to internal jugular vein shunt for managing hypoxemia after a cavopulmonary shunt - Garg, P.; Talwar, S.; Rajashekar, P.; Kothari, S.S.; Gulati, G.S.; Airan, B. (Annals of Thoracic Surgery, 2012)
In the present report, we discuss a patient who developed persistent hypoxemia after an attempt at Fontan completion failed. As a bail-out procedure, a left common carotid artery to left internal jugular vein shunt was constructed, after which the hypoxemia was relieved. © 2012 The Society of Thoracic Surgeons.
Keywords: anticonvulsive agent; adolescent; agitation; angiography; arteriovenous fistula; arteriovenous shunt; artery catheterization; article; cardiopulmonary bypass; case report; cavopulmonary connection; common carotid artery; cyanosis; dextrocardia; disorientation; Doppler echocardiography; dyspnea; echocardiography; femoral artery; focal epilepsy; Fontan procedure; Glenn shunt; heart catheterization; heart ventricle septum defect; human; hypoxemia; internal jugular vein; lung angiography; male; priority journal; pulmonary valve stenosis; sternotomy

Brain abscess in cyanotic congenital heart disease: A preventable complication with heavy financial burden and poor outcome - Arshad, M.S.; Aslam, M.; Rubab, S. (Medical Forum Monthly, 2012)
Objectives: To evaluate the financial burden and outcome of the children with brain abscess and underlying congenital cyanotic heart disease. To emphasize the need of early diagnosis and surgery of congenital cyanotic heart disease. Study Design: Cross Sectional Descriptive Study. Place and Duration of Study: This study was conducted at the department of paediatric cardiology The Children's Hospital and The Institute of Child Health, Multan from February 2010 to January 2012. Patients and Methods: All the patients presenting with brain abscess and having underlying congenital heart disease were included in the study. All the patients underwent transthoracic echocardiography and computed tomography (CT) scan of the brain. Data was taken on a written proforma after proper consent. Results: A total of 58 patients with cyanotic congenital heart disease presented with CNS manifestations including headache, fever, focal neurological signs, fits or altered sensorium during the study period. Out of these 24 turned out to have brain abscess. Multiple brain abscesses were found in 7 patients. All the patients were given broad spectrum IV antibiotics. 19 of the patients required surgical intervention. Repeat CT scan was performed in all the patients. Only 5 patients recovered without any neurological sequalae.7 patients expired during hospital stay. All of the remaining 12 patients survived but with some permanent neurological deficit.IV antibiotics, supportive treatment, CT scan, other laboratory investigations and surgery, all have a lot of cost. Around 1500 to 2000 US $, on an average, were spent by the government, on one patient during hospital stay. Conclusion: The only way to avoid CNS complications of CCHD is early diagnosis and early surgical treatment. But unfortunately, in this country because of lake of paediatric cardiology services and deficiency of paediatric cardiac surgery centers, corrective surgery of congenital cyanotic heart disease is delayed. It increases the risk of brain abscess formation which in turn leads to excessive financial burden on government resources and also increases the risk of long term neurological sequalae. Establishment of more and more paediatric cardiac surgery centers in this country is urgently required.
Keywords: ceftriaxone; metronidazole; vancomycin; adolescent; antibiotic therapy; aphasia; article; blindness; brain abscess; child; computer assisted tomography; craniotomy; cross-sectional study; cyanotic heart disease; descriptive research; early diagnosis; facial nerve paralysis; Fallot tetralogy; fever; finance; government; great vessels transposition; headache; health care cost; heart ventricle septum defect; hemiplegia; hospitalization; human; major clinical study; neuroimaging; outcome assessment; preschool child; pulmonary valve atresia; pulmonary valve stenosis; school child; sensory system; transthoracic echocardiography; treatment response; tricuspid valve atresia

Heart for bonding: A new protocol of care for hypoplastic left heart syndrome - Parker, M.E.; Bradshaw, W.T.; Smith, H.R. (Neonatal Network, 2012)
There are significant challenges involved in the perinatal and postnatal care of an infant with hypoplastic left heart syndrome (HLHS) and the infant's family. In the blink of an eye, the perfect child is lost, and a fragile infant is about to join the family. This case study and discussion is an overview of HLHS, a family's desire to make the birth of their infant normal, and how that desire initiated a change in philosophy and practice in our neonatal intensive care unit. Keywords: hypoplastic left heart syndrome, HLHS, family centered care, parent-infant bonding, breastfeeding. © 2012 Springer Publishing Company.
Keywords: adult; article; case report; female; human; hypoplastic left heart syndrome; methodology; newborn nursing; nursing; object relation; palliative therapy; pregnancy; prenatal diagnosis

Malformations detected by abdominal ultrasound in children with congenital heart disease - Rosa, R.C.M.; Fabiano Machado Rosa, R.; Flores, J.A.M.; Golendziner, E.; De Oliveira, C.A.V.; Varella-Garcia, M.; Paskulin, G.A.; Zen, P.R.G. (Arquivos Brasileiros de Cardiologia, 2012)
Background: Extracardiac malformations may be present in patients with congenital heart disease (CHD), bringing greater risk of comorbidity and mortality. Objective: Verify frequency and types of abdominal abnormalities detected in children with and without CHD through abdominal ultrasound (AUS), compare the patients in relation to their dysmorphic/cytogenetic findings and perform an estimative of the cost-effectiveness of the screening through AUS. Methods: We conducted a cross-sectional study with a control cohort. The cases consisted of patients with CHD admitted for the first time in a pediatric intensive care unit; the controls consisted of children without CHD who underwent AUS at the hospital shortly thereafter a case. All patients with CHD underwent AUS, high-resolution karyotype and fluorescence in situ hybridization (FISH) for microdeletion 22q11.2. Results: AUS identified clinically significant abnormalities in 12.2% of the cases and 5.2% of controls (p= 0.009), with a power of significance of 76.6%. Most malformations with clinical significance were renal anomalies (10.4% in cases and 4.9% in controls; p= 0.034). In Brazil, the cost of an AUS examination for the Unified Health System is US$ 21. Since clinically significant abnormalities were observed in one in every 8.2 CHD patients, the cost to identify an affected child was calculated as approximately US$ 176. Conclusion: Patients with CHD present a significant frequency of abdominal abnormalities detected by AUS, an inexpensive and noninvasive diagnostic method with good sensitivity. The cost of screening for these defects is considerably lower than the cost to treat the complications of late diagnoses of abdominal malformations such as renal disease.
Keywords: aortic coarctation; article; atrioventricular septal defect; child; chromosome analysis; chromosome deletion 22q11; cohort analysis; congenital heart disease; controlled study; cost effectiveness analysis; cross-sectional study; cyanotic heart disease; Down syndrome; echography; Fallot tetralogy; female; fluorescence in situ hybridization; heart atrium septum defect; heart right ventricle double outlet; heart ventricle septum defect; hospitalization; human; hypoplastic left heart syndrome; infant; karyotyping; kidney malformation; lung vein drainage anomaly; major clinical study; male; newborn; patent ductus arteriosus; pulmonary valve atresia

Risk factors for neurodevelopmental impairments in school-age children after cardiac surgery with full-flow cardiopulmonary bypass - Von Rhein, M.; Dimitropoulos, A.; Valsangiacomo Buechel, E.R.; Landolt, M.A.; Latal, B. (Journal of Thoracic and Cardiovascular Surgery, 2012)
Objective: To determine the risk factors for adverse neurodevelopmental outcomes in school-age children after full flow open-heart surgery for congenital heart disease. Methods: The outcome was assessed in 117 children without a genetic comorbidity at a mean age of 10.4 ± 2.5 years. Intelligence was assessed using the Raven's Progressive Matrices and neuromotor function using the Zurich Neuromotor Assessment. Risk factors were retrieved from detailed chart review. Results: The mean intelligence score was 89 ± 16, significantly lower than the norm (P < .001). Cerebral palsy was diagnosed in 10% of patients. Poor neuromotor performance (less than p10) was present in 15% to 20% of the children, depending on the motor task (all P < .001). Pure motor and static balance performance was also significantly impaired when patients with cerebral palsy were excluded (P < .01). Intelligence was only related to socioeconomic status (P = .006), and neuromotor outcome was related to the length of hospital stay and postoperative neurologic abnormalities (P < .03). The extracorporeal circulation time was related to adaptive fine motor performance (P = .05). All other variables were not related to outcome. Conclusions: Children without a genetic comorbidity are at risk of long-term intellectual and motor impairments also after full-flow cardiac repair. Surgery-related parameters play a less important role for adverse outcomes than postoperative complications. Our findings stress the importance of specialized follow-up assessments for all children with CHD undergoing open heart surgery. Copyright © 2012 by The American Association for Thoracic Surgery.
Keywords: adolescent; age; aortic coarctation; aortic stenosis; article; body equilibrium; cardiopulmonary bypass; cerebral palsy; child; clinical assessment tool; cohort analysis; congenital heart disease; cor triatriatum; coronary artery fistula; extracorporeal circulation; Fallot tetralogy; female; heart arrhythmia; heart atrium septum defect; human; intellectual impairment; intelligence test; length of stay; lung vein drainage anomaly; major clinical study; male; medical record review; mitral valve stenosis; morbidity; motoneuron; motor dysfunction; motor performance; neurologic disease; open heart surgery; outcome assessment; preschool child; priority journal; pulmonary valve atresia; pulmonary valve stenosis; raven progressive matrices and neuromotor function; risk factor; school child; socioeconomics; tricuspid valve atresia; zurich neuromotor assessment

Thrombotic complications and thromboprophylaxis across all three stages of single ventricle heart palliation - Manlhiot, C.; Brandão, L.R.; Kwok, J.; Kegel, S.; Menjak, I.B.; Carew, C.L.; Chan, A.K.; Schwartz, S.M.; Sivarajan, V.B.; Caldarone, C.A.; Van Arsdell, G.S.; McCrindle, B.W. (Journal of Pediatrics, 2012)
Objectives: To describe the incidence of thrombotic complications across all 3 stages of single ventricle palliation and the association between thromboprophylaxis use and thrombotic risk. Study design: Two separate cross-sectional studies were performed that included 195 patients born between 2003-2008 and 162 patients who underwent Fontan after 2000. Results: The incidence of thrombotic complications was 40% and 28% after initial palliation and superior cavopulmonary connection (SCPC), respectively; 5-year freedom from thrombotic complications after Fontan was 79%. Thromboprophylaxis was initiated for 70%, 46%, and 94% of patients after initial palliation, SCPC, and Fontan, respectively. Thromboprophylaxis with enoxaparin (vs no thromboprophylaxis) was associated with a reduction in risk of thrombotic complications after initial palliation (hazard ratio [HR] 0.5, P = .05) and SCPC (HR 0.2, P = .04). Thromboprophylaxis with warfarin was associated with a reduction in thrombotic complications after Fontan (HR 0.27, P = .05 vs acetylsalicylic acid; HR 0.18, P = .02 vs no thromboprophylaxis). Thrombotic complications were associated with increased mortality after initial palliation (HR 5.5, P < .001) and SCPC (HR 12.5, P < .001). Three patients experienced major bleeding complications without permanent sequelae (2 enoxaparin, 1 warfarin). Conclusions: Given the negative impact of thrombotic complications on survival, the low risk of serious bleeding complications, and the association between thromboprophylaxis and lowered thrombotic complication risk across all 3 palliative stages, routine use of thromboprophylaxis from the initial palliation to the early post-Fontan period in this population may be indicated. © 2012 Mosby, Inc.
Keywords: acetylsalicylic acid; enoxaparin; warfarin; article; bleeding; brain hematoma; female; Fontan procedure; human; infant; initial thrombosis palliation; major clinical study; male; mortality; newborn; portocaval shunt; priority journal; risk reduction; single ventricle heart palliation; superior cavopulmonary connection; thrombosis; thrombosis prevention

50 Years Ago in The Journal of Pediatrics: Growth Disturbance in Congenital Heart Disease - Gidding, S.S. (Journal of Pediatrics, 2012)
Keywords: article; congenital heart disease; dysphagia; growth disorder; heart single ventricle; hemodynamics; human; priority journal; prognosis; quality of life; vocal cord paralysis

B-type natriuretic peptide at the early stage of univentricular circulation reflects inadequate adaptation to volume overload - Inuzuka, R.; Tatebe, S.; Wakiguchi, S.; Nakajima, H.; Ohtsu, H.; Dimopoulos, K.; Aotsuka, H. (International Journal of Cardiology, 2012)
Background: Recent studies showed that children with univentricular heart have elevated plasma B-type natriuretic peptide (BNP) levels prior to bidirectional cavopulmonary anastomosis (BDCPA). However, it remains to be established whether BNP levels reflect the degree of hemodynamic overload and relate to long-term outcome in univentricular circulation. Methods: Fifty one consecutive children with functionally univentricular heart prior to BDCPA were studied. All patients underwent cardiac catheterization and BNP measurement. Ventricular end-systolic wall stress (ESWS) and end-diastolic wall stress (EDWS) were calculated from cardiac catheterization data. Results: Median age was 1.1 years and 34% were female. Median BNP concentration was 90.4 pg/ml. Patients with high BNP (≥ 100 pg/ml) had higher pulmonary to systemic flow ratio (p = 0.014), a greater end-diastolic volume (p = 0.009), more severe atrioventricular valve regurgitation (p = 0.02) and lower ventricular mass to end-diastolic volume ratio (p = 0.006). BNP levels strongly related to EDWS (r = 0.75, p < 0.0001) and ESWS (r = 0.63, p < 0.0001). During median follow-up period of 3.2 years, 15 patients died and one underwent heart transplantation for refractory heart failure. On multivariate Cox regression analysis, high BNP concentration was an independent predictor of death or transplantation (HR 3.05, CI: 1.06-8.83, p = 0.04). Conclusions: High BNP concentration at the first palliative stage towards Fontan circulation reflects high wall stress due to high volume load and insufficient ventricular hypertrophy. Moreover, high BNP levels at this stage were independently related to long-term outcome. BNP may be used as a guide to identify patients with high workload due to inadequate adaptation to hemodynamic load, who are at high risk. © 2011 Elsevier Ireland Ltd.
Keywords: brain natriuretic peptide; article; cardiovascular parameters; cavopulmonary connection; child; child death; circulation; clinical article; end diastolic wall stress; female; follow up; Fontan procedure; heart catheterization; heart failure; heart hemodynamics; heart single ventricle; heart transplantation; heart valve regurgitation; heart volume overload; heart work; high risk patient; human; infant; male; observational study; patient identification; preschool child; priority journal; proportional hazards model; pulmonary to systemic flow ratio; univentricular circulation; ventricular end systolic wall stress; ventricular mass to end diastolic volume ratio; wall stress

MRI-guided ablation of wide complex tachycardia in a univentricular heart - Reiter, T.; Ritter, O.; Nordbeck, P.; Beer, M.; Bauer, W.R. (World Journal of Cardiology, 2012)
Magnetic resonance imaging can be used for prepro-cedural assessment of complex anatomy for radiofre-quency (RF) ablations, e.g., in a univentricular heart. This case report features the treatment of a young patient with a functionally univentricular heart who suf-fered from persistent sudden onset tachycardia with wide complexes that required RF ablation as treatment. © 2012 Baishideng.
Keywords: acetylsalicylic acid plus dipyridamole; adenosine; ajmaline; gadolinium; isoprenaline; methylphenidate; adolescent; angina pectoris; article; attention deficit disorder; case report; dizziness; electrocardiography; follow up; Fontan procedure; heart ejection fraction; cardiac index; heart single ventricle; heart ventricle septum defect; human; magnetic resonance angiography; male; nuclear magnetic resonance imaging; radiofrequency ablation; tachycardia; tricuspid valve atresia; aggrenox; medikinet; 3T Trio

Twisted cardiovascular cages for intravascular axial flow blood pumps to support the Fontan physiology - Throckmorton, A.L.; Downs, E.A.; Hazelwood, J.A.; Monroe, J.O.; Chopski, S.G. (International Journal of Artificial Organs, 2012)
Failing single ventricle physiology represents an ongoing challenge in mechanical assist device development, requiring pressure augmentation in the cavopulmonary circuit, reduction of systemic venous pressure, and increased cardiac output to achieve hemodynamic stabilization. To meet these requirements, we are developing a percutaneously-placed, axial flow blood pump to support ailing single ventricle physiology in adolescents and adults. We have modified the outer cage of the device to serve as both a protective and functional design component. This study examined the performance of 3 cage geometries with varying directions of filament twist using numerical simulations and hydraulic experiments. All 3 cage and pump models performed in acceptable ranges to support Fontan patients. The cage design employing filaments that are twisted in the opposite direction to the impeller blades and in the direction of the diffuser blades (against-with) demonstrated superior performance by generating a pressure rise range of 5-38 mm Hg of flow rates of 0.5-6 l/min at rotational speeds of 5000-7000 rpm. The blood damage indices for all of the cages were found to be well below 2%, and the scalar stress levels were below 200 Pa. This study represents ongoing progress in the development of the impeller and cage assembly. Validation of the results will continue in experiments with blood bag evaluation as well as by particle image velocimetry measurements. © 2012 Wichtig Editore.
Keywords: article; blood flow velocity; blood pump; computational fluid dynamics; energy transfer; Fontan procedure; geometry; heart assist device; hydraulic conductivity; intravascular axial flow blood pump; pressure; simulation; physiological stress; validation process

Mortality and neurodevelopmental outcome at 1 year of age comparing hybrid and Norwood procedures - Knirsch, W.; Liamlahi, R.; Hug, M.I.; Hoop, R.; von Rhein, M.; Prêtre, R.; Kretschmar, O.; Latal, B. (European Journal of Cardio-thoracic Surgery, 2012)
Objectives: Neonates with hypoplastic left heart syndrome (HLHS) are at risk of high mortality and neurodevelopmental morbidity. As an alternative to Norwood-type stage I palliation, the hybrid procedure has been developed. It consists of bilateral pulmonary artery banding, catheter-based stenting of the arterial duct and balloon atrioseptostomy and delays open-heart surgery. Thus, it may be associated with a better outcome. The aim of this study was to determine the mortality and neurodevelopmental outcome in patients with HLHS and other univentricular heart (UVH) defects treated with hybrid or Norwood procedures. Methods: Thirty-one children (18 males) with HLHS and other UVH defects undergoing Norwood or hybrid procedure between 2004 and 2008 were consecutively enrolled. Mortality and neurodevelopmental outcome at 1 year of age were determined. RESULTS: One-year mortality was 36% (31% in the hybrid vs. 39% in the Norwood group, P = 0.71). Predictors of mortality were lower birth weight (P = 0.02), older age at first procedure (P = 0.02) and smaller size of ascending aorta (P = 0.05). Overall, median psychomotor development index (PDI) and mental development index (MDI) of the Bayley Scales of Infant Development II were lower than the norm of 100 [PDI 57 (49-99), P < 0.001; MDI 91 (65-109), P = 0.002]. No effect of surgical treatment on neurodevelopmental outcome was found. Predictors of impaired motor outcome were length of hospital stay (LOHS) (P = 0.01), lower body weight at second procedure (P = 0.004) and female sex (P = 0.01). Predictors of impaired cognitive outcome were longer mechanical ventilation time (P = 0.03), intensive care unit stay (P = 0.04) and LOHS (P < 0.001), respectively. Conclusions: Mortality at 1 year of age is comparable between patients undergoing hybrid and Norwood procedures. Early neurodevelopmental outcome is significantly impaired in patients with both HLHS and other UVH defects. Multicentre randomized studies are needed to determine the long-term neurodevelopmental outcome of children treated with the hybrid procedure. © The Author 2012. Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: adult; article; artificial ventilation; ascending aorta; birth weight; child; clinical article; cognitive defect; female; heart single ventricle; heart surgery; hospitalization; human; hybrid procedure; hypoplastic left heart syndrome; intensive care unit; intermethod comparison; length of stay; male; mental development; nerve cell differentiation; Norwood procedure; preschool child; priority journal; psychomotor development; school child

Influence of surgical arch reconstruction methods on single ventricle workload in the Norwood procedure - Itatani, K.; Miyaji, K.; Qian, Y.; Liu, J.L.; Miyakoshi, T.; Murakami, A.; Ono, M.; Umezu, M. (Journal of Thoracic and Cardiovascular Surgery, 2012)
Objective: The study objective was to evaluate various types of Norwood arch reconstruction methods and to show the factors that affect the cardiac workload of the single ventricle. The Norwood procedure is one of the most challenging congenital heart surgeries. Several aortic arch reconstruction techniques have been reported to avoid recoarctation, ensure coronary perfusion, and improve long-term outcomes. Inside the arch, complicated turbulent flow is generated; however, little is known about the cause of the disadvantageous inefficient flow and the surgical techniques to avoid it. Methods: We created patient-specific computational hemodynamic models of 9 patients who underwent different types of arch reconstruction methods. Four patients had aortic atresia, and 5 patients had aortic stenosis. Flow profiles were defined by echocardiography data corrected with body surface area. Turbulent pulsatile flow was analyzed with the finite volume method. Flow energy loss was calculated to estimate cardiac workload, and wall shear stress was calculated to estimate vessel wall stiffness increase. Results: Recoarctation and acute arch angles increased wall shear stress and energy loss. In the patients with aortic atresia, a longitudinal incision toward the descending aorta was effective in creating a smooth arch angle. In the patients with aortic stenosis, arch repair with the Damus-Kaye-Stansel procedure in a single anastomotic site was effective in creating sufficient anastomosis space and a smooth arch angle. Conclusions: Creation of a large anastomotic space and a smooth aortic arch angle reduced wall shear stress and energy loss, and should improve long-term cardiac performance after the Norwood procedure. Copyright © 2012 by The American Association for Thoracic Surgery.
Keywords: aorta atresia; aortic coarctation; aortic flow; aortic stenosis; aortic arch surgery; arterial stiffness; article; atresia; blood flow velocity; blood vessel graft; body surface; cardiac workload; child; clinical article; echocardiography; heart hemodynamics; heart single ventricle; heart work; human; Norwood procedure; preschool child; priority journal; pulsatile flow; shear stress

Quality of life of pediatric cardiac patients who previously required extracorporeal membrane oxygenation - Costello, J.M.; O'Brien, M.; Wypij, D.; Shubert, J.; Salvin, J.W.; Newburger, J.W.; Laussen, P.C.; Arnold, J.H.; Fynn-Thompson, F.; Thiagarajan, R.R. (Pediatric Critical Care Medicine, 2012)
OBJECTIVES: We sought to assess quality of life of pediatric cardiac extracorporeal membrane oxygenation survivors. We hypothesized that these patients would have decreased quality of life when compared to that of a general U.S. population sample. DESIGN: Cross-sectional study. SETTING: Patient homes and Children's Hospital Boston. PATIENTS: Cardiac extracorporeal membrane oxygenation survivors currently 5-18 yrs old. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Quality of life was assessed by parent proxy report using the Child Health Questionnaire Parent Form 50 and was compared to that of a general U.S. population sample and other cardiac populations. Factors associated with lower quality of life were sought. Physical summary scores for 41 cardiac extracorporeal membrane oxygenation survivors were lower than the mean of the general population sample (42.4 ± 16.4 vs. 53.0 ± 8.8; p < .001) but similar to those of children with Fontan physiology or an automatic implantable cardioverter defibrillator. Psychosocial summary scores in extracorporeal membrane oxygenation patients were not different from those of the general population (48.2 ± 11.8 vs. 51.2 ± 9.1; p = .11) or of other cardiac samples. Postcardiotomy extracorporeal membrane oxygenation, more noncardiac operations, total intensive care and hospital days, noncardiac medical conditions, medications, and the need for physical, occupational, or speech therapy were associated with low physical summary scores. More noncardiac operations, noncardiac medical conditions, and the need for special education, physical, occupational, or speech therapy were associated with low psychosocial summary scores. CONCLUSIONS: In pediatric cardiac extracorporeal membrane oxygenation survivors, the physical component of health-related quality of life is lower than that of the general population but similar to that of patients with complex cardiac disease, whereas psychosocial quality of life is similar to that of the general population and of other pediatric cardiac populations. Copyright © 2012 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: adolescent; adult; article; cardiac patient; child; Child Health Questionnaire Parent Form 50; controlled study; defibrillator; extracorporeal oxygenation; female; heart disease; human; intensive care unit; length of stay; major clinical study; male; occupational therapy; physiotherapy; preschool child; priority journal; psychosocial care; quality of life; questionnaire; school child; scoring system; special education; speech therapy; survivor; treatment outcome; United States

Partial anomalous left pulmonary artery along with aortic coarctation in an infant with kabuki syndrome - Bhat, A.H.; Davenport, J.; Cocalis, M. (Echocardiography, 2012)
We report an antenatally diagnosed fetal coarctation delivered prematurely and confirmed to have coarctation as well as additional nonobstructing anomalous left pulmonary artery branch (aLPA) from right pulmonary artery (RPA) and significant dysmorphic features. The baby underwent an uncomplicated arch repair, but had numerous multisystem and growth related issues prompting a diagnosis of Kabuki syndrome (KS) at 1 year of age. While coarctation and hypoplastic left heart syndrome are observed in this syndrome, this is the second reported case of aLPA in KS and the first with the forme fruste of left-sided obstruction as well as aLPA in this group of patients. (Echocardiography 2012;29:E145-E147) This case report describes an unusual constellation of aortic coarctation diagnosed antenatally, an unusual anatomic variant of pulmonary artery anatomy wherein the left lower lung was supplied by an anomalous accessory left pulmonary artery arising from the right pulmonary artery and clinical diagnosis of Kabuki syndrome in early childhood. © 2012, Wiley Periodicals, Inc.
Keywords: prostaglandin; SOS protein; aortic coarctation; aortic valve; aortic arch surgery; article; brachydactyly; case report; cesarean section; clinodactyly; cryptorchism; echocardiography; fetus echography; gestational age; heart catheterization; HELLP syndrome; human; hypoplastic left heart syndrome; infant; inguinal hernia; joint laxity; Kabuki makeup syndrome; male; mitral valve; Noonan syndrome; premature labor; prenatal diagnosis; priority journal; pulmonary artery malformation; transthoracic echocardiography

Exploring the seasonality of birth defects in the New York State Congenital Malformations Registry - Caton, A.R. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2012)
Background Examining seasonal patterns of birth defects may help to identify environmental risk factors. Because the teratogenic window for most birth defects is during gestational weeks 3 to 8, investigating exposures closer to the timing of conception is important. However, studies are usually based on month of birth, which is not the biologically relevant exposure period and does not account for differences in gestational length. We aimed to determine whether the occurrence of birth defects varied by month of conception using the population-based New York State Congenital Malformations Registry (CMR). Methods: We merged live birth certificates (n = 2,044,091) with CMR records for mothers residing in New York State, excluding New York City, for the years 1992 through 2006. We categorized birth defects according to the National Birth Defects Prevention Network guidelines and performed Cochran-Armitage trend, Hewitt-Rogerson, and Walter-Elwood tests on month of conception and chi-square tests on season of conception. We graphed seasonal distributions and seasonality test results. We performed stratified analyses by maternal and infant characteristics. Results: Of 42 groups examined in the 15-year period, 24 (57%) had at least one statistically significant test result, suggesting a trend or seasonal variation: Cochran-Armitage (18), Hewitt-Rogerson (17), Walter-Elwood (4), and chi-square (5). Ventricular septal defect showed the most consistent results: Cochran-Armitage (p = 0.0006), Hewitt-Rogerson (December to May; p = 0.0130), Walter-Elwood (March 14; p = 0.0027), and chi-square (winter; p = 0.0046). Congenital cataract, pulmonary valve atresia/stenosis, coarctation of aorta, biliary atresia, and renal agenesis or hypoplasia had at least three significant tests. Discussion: These results may help to generate hypotheses about environmental factors that vary by season for further studies. © 2012 Wiley Periodicals, Inc.
Keywords: amnion band syndrome; anencephalus; anophthalmia; anus atresia; aortic coarctation; aortic valve stenosis; article; bile duct atresia; birth certificate; congenital malformation; chi square test; choana atresia; cleft lip; cleft palate; Cochran Armitage trend; congenital cataract; congenital diaphragm hernia; congenital hip dislocation; congenital hydrocephalus; congenital malformations registry; disease registry; Down syndrome; Ebstein anomaly; encephalocele; endocardial cushion defect; epispadias; esophagus atresia; Fallot tetralogy; female; fetal alcohol syndrome; gastroschisis; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; Hewitt Rogerson test; Hirschsprung disease; human; hypoplastic left heart syndrome; hypospadias; infant; intestine stenosis; kidney agenesis; kidney hypoplasia; limb reduction defect; live birth; major clinical study; male; microcephaly; microphthalmia; microtia; obstructive uropathy; omphalocele; patent ductus arteriosus; practice guideline; priority journal; pulmonary valve atresia; pulmonary valve stenosis; pylorus stenosis; seasonal variation; spinal dysraphism; statistical analysis; summer; tracheoesophageal fistula; tricuspid valve atresia; trisomy 13; trisomy 18; Walter Elwood test; winter

Acute ischemic stroke in a child with cyanotic congenital heart disease due to non-compliance of anticoagulation - Mohammad, M.; James, A.F.; Qureshi, R.S.; Saraf, S.; Ahluwalia, T.; Mukherji, J.D.; Kole, T. (World Journal of Emergency Medicine, 2012)
BACKGROUND: Stroke is a common presentation in geriatric patients in emergency department but rarely seen in pediatric patients. In case of acute ischemic stroke in pediatric age group, management is different from that of adult ischemic stroke where thrombolysis is a good option. METHODS: We report a case of a 17-year-old male child presenting in emergency with an episode of acute ischemic stroke causing left hemiparesis with left facial weakness and asymmetry. The patient suffered from cyanotic congenital heart disease for which he had undergone Fontan operation previously. He had a history of missing his daily dose of warfarin for last 3 days prior to the stroke. RESULTS: The patient recovered from acute ischemic stroke without being thrombolyzed. CONCLUSION: In pediatric patients, acute ischemic stroke usually is evolving and may not require thrombolysis. © 2012 World Journal of Emergency Medicine.
Keywords: enalapril; low molecular weight heparin; warfarin; adolescent; anticoagulation; article; brain ischemia; case report; congenital heart disease; cyanotic heart disease; echocardiography; emergency ward; face asymmetry; face muscle; Fontan procedure; hemiparesis; hospital patient; human; image analysis; limb weakness; male; medical history; muscle weakness; nuclear magnetic resonance imaging; treatment refusal

Ultrasound contrast and real-time perfusion in conjunction with supine bicycle stress echocardiography for comprehensive evaluation of surgically corrected congenital heart disease - Kutty, S.; Olson, J.; Danford, C.J.; Sandene, E.K.; Xie, F.; Fletcher, S.E.; Erickson, C.C.; Kugler, J.D.; Danford, D.A.; Porter, T.R. (European Heart Journal Cardiovascular Imaging, 2012)
Aims: We sought to evaluate the efficacy of ultrasound contrast (UC) and low mechanical index real-time perfusion (RTP) in the haemodynamic and anatomic assessment of repaired congenital heart disease (CHD) at rest and during supine bicycle stress echocardiography (BSE). Methods and results: Patients with CHD (n = 51, median age 21.5 years) were prospectively studied. All had compromised image quality, 20 (39%) had arrhythmias, and 10 (20%) had pacemakers. RTP was performed at rest and during BSE using Definity and Contrast Pulse Sequencing, with assessment of Doppler pressure gradients. Diagnoses included tetralogy of Fallot (n = 27), transposition of the great arteries (TGA) atrial switch (n = 10), TGA arterial switch (n = 2), aortic valve disease (n = 4), Fontan (n = 4), and Kawasaki disease (n = 4). UC with RTP improved endocardial border definition, with increased number of left ventricular (LV) and right ventricular (RV) segments visualized at rest (P < 0.0001) and during stress. LV ejection fraction (EF) and RV fractional area change (FAC) were measurable at rest and peak stress, RV FAC correlating closely with same-day magnetic resonance EFs (r = 0.72; P < 0.001). UC enhanced Doppler signals, enabling subpulmonary ventricular systolic pressure measurements at rest and stress. In six patients, marked elevations of subpulmonary ventricular systolic pressure were detected with UC during BSE, and quantifiable ventricular dysfunction. No adverse events occurred, other than transient low back pain in one patient. Conclusion: UC at rest and with supine BSE enables safe and comprehensive assessment of anatomy, haemodynamics, and biventricular functional and perfusion reserve in adolescents and young adults with surgically modified CHD. ClinicalTrials.gov Identifier: NCT00861848. Published on behalf of the European Society of Cardiology. All rights reserved. © The Author 2011.
Keywords: NCT00861848; echo contrast medium; adolescent; adult; aortic valve disease; article; bicycle; blood pressure measurement; cardiac imaging; cardiovascular magnetic resonance; clinical trial; congenital heart disease; contrast enhancement; Doppler flowmetry; Fallot tetralogy; female; Fontan procedure; great vessels transposition; heart arrhythmia; heart hemodynamics; heart left ventricle; heart left ventricle ejection fraction; heart right ventricle; heart ventricle contractility; heart ventricle function; heart ventricle pressure; human; image quality; low back pain; low mechanical index real time perfusion; major clinical study; male; mucocutaneous lymph node syndrome; cardiac rhythm management device; priority journal; prospective study; rest; stress echocardiography; supine bicycle stress echocardiography; supine position; systolic blood pressure

Anesthesia for the adult patient with an unrepaired congenital cyanotic heart defect: A case report - Cosgrove, M.S. (AANA Journal, 2012)
Adult congenital heart disease, previously considered a rare comorbidity, is increasingly becoming a reality for today's anesthesia providers. Improvements in prenatal diagnosis, sophisticated surgical techniques and equipment, advances in pediatric critical care, enhanced efficacy of cardiovascular pharmacologic agents, and an overall increase in postrepair survival rates have resulted in an estimated population of approximately 800,000 adults with congenital heart disease. Despite successful surgical repair or palliation, these individuals present the anesthesia provider with a multitude of challenges. Individualized care of these fragile patients should be approached with a keen understanding of the patient's underlying cardiac anomaly. This case report chronicles the anesthetic care of a 36-year-old woman presenting for left-sided ureteroscopy with laser lithotripsy and stent placement. Her medical history was remarkable for the presence of complex congenital heart disease consisting of multiple anomalies: a double-outlet right ventricle, transposition of the great arteries, pulmonary stenosis, atrial septal defect, and a hypoplastic left ventricle with concomitant mitral valve atresia. General anesthesia was successfully administered, with meticulous attention given to maintenance of systemic vascular resistance to minimize shunting, oxygenation, administration of preprocedure antibiotics, and judicious replacement of intravenous fluids via air-filtered tubing.
Keywords: acetylsalicylic acid; epinephrine; amiodarone; ampicillin; analgesic agent; aspartate aminotransferase; bilirubin; creatinine; digoxin; enalapril; fentanyl; ferrous sulfate; gentamicin; glycopyrronium; infusion fluid; ketamine; levothyroxine; midazolam; morphine sulfate; neostigmine; ondansetron; rocuronium; sevoflurane; ablation therapy; adult; anesthesia induction; antibiotic prophylaxis; article; cardiomegaly; case report; cleft lip; congestive heart failure; conservative treatment; cyanotic heart disease; cystoscopy; drug hypersensitivity; female; general anesthesia; great vessels transposition; heart arrest; heart atrium flutter; heart atrium septum defect; heart left anterior bundle branch block; heart left ventricle hypertrophy; heart right bundle branch block; heart right left shunt; heart right ventricle double outlet; heart ventricle fibrillation; human; hypoplastic left heart syndrome; hypothyroidism; laser lithotripsy; leukocyte count; lymphocyte count; mean corpuscular volume; mitral valve atresia; muscle relaxation; neutrophil count; oxygen saturation; oxygen therapy; postoperative nausea and vomiting; proteinuria; pulmonary valve stenosis; self report; shunting; stent; systemic vascular resistance; systolic heart murmur; thorax radiography; ureter stone; ureteroscopy

Sex and age differences in body-image, Self-Esteem, and Body mass index in adolescents and adults after single-ventricle palliation - Pike, N.A.; Evangelista, L.S.; Doering, L.V.; Eastwood, J.-A.; Lewis, A.B.; Child, J.S. (Pediatric Cardiology, 2012)
Single-ventricle congenital heart disease (SVCHD) requires multiple palliative surgical procedures that leave visible surgical scars and physical deficits, which can alter body-image and self-esteem. This study aimed to compare sex and age differences in body-image, selfesteem, and body mass index (BMI) in adolescents and adults with SVCHD after surgical palliation with those of a healthy control group. Using a comparative, cross-sectional design, 54 adolescent and adult (26 male and 28 female) patients, age 15-50 years, with SVCHD were compared with 66 age-matched healthy controls. Body-image and self-esteem were measured using the Multidimensional Body-Self Relations Questionnaire-Appearance Scale and Rosenberg Self-Esteem Scale. Height and weight were collected from retrospective chart review, and BMI was calculated. Female adolescents and adult patients with SVCHD reported lower body image compared with males patients with SVCHD and healthy controls (p = 0.003). Specific areas of concern were face (p = 0.002), upper torso or chest (p = 0.002), and muscle tone (p = 0.001). Patients with SVCHD who were \21 years of age had lower body image compared with healthy controls (p = 0.006). Self-esteem was comparable for both patients with SVCHD and healthy peers. There were no sex differences in BMI; BMI was higher in subjects[21 years of age (p = 0.01). Despite the similarities observed in selfesteem between the two groups, female patients with SVCHD\21 years of age reported lower perceived bodyimage. Our findings support the need to recognize poor psychological adjustment related to low self-esteem in patients with SVCHD; female patients warrant increased scrutiny. Strategies to help patients with SVCHD cope with nonmodifiable aspects of body-image during the difficult adolescent-to-young adult years may potentially enhance self-esteem and decrease psychological distress. © Springer Science+Business Media, LLC 2012.
Keywords: adolescent; adult; age; article; body height; body image; body mass; body weight; controlled study; face; female; heart single ventricle; heart surgery; human; major clinical study; male; medical record review; muscle tone; questionnaire; self esteem; sex difference; thorax; trunk

Increase in N-Terminus-Pro-B-Type natriuretic peptide during exercise of patients with univentricular heart after a total cavopulmonary connection - Hager, A.; Christov, F.; Hess, J. (Pediatric Cardiology, 2012)
An increase in N-terminus pro-B-type natriuretic peptide (NT-proBNP) during exercise is related to myocardial ischemia, myocardial dysfunction, and inflammatory stress. Its value for patients with a univentricular heart after total cavopulmonary connection (TCPC) is unknown. For 66 patients with TCPC, a cardiopulmonary exercise test was performed. Venous NT-proBNP samples were drawn with the patient at rest and then 2-3 min after peak exercise. The median NT-proBNP during rest was 82 ng/l (range, 11-2,554 ng/l), with 22 patients above the upper reference limit. A higher NT-proBNP during rest was related to a worse peak oxygen uptake (peak VO2), a higher ventilatory equivalent (VE/VCO2 slope), and a need for diuretics administration. A small but significant increase in NT-proBNP during exercise at 6 ng/l (range, 0-314 ng/l) was related mainly to its resting value. The relative increase was solely related to a higher body mass and not to any of the investigated functional parameters. Usually, NT-proBNP during rest is not elevated in TCPC patients. If so, it is a valuable predictor of cardiac function. During exercise, only a minor increase in NT-proBNP occurs. Its extent is not related to any of the investigated functional parameters. Maybe the filling restriction from the lungs prevents atrial and ventricular overload as well as BNP secretion in TCPC patients.
Keywords: amino terminal pro brain natriuretic peptide; amiodarone; anticoagulant agent; beta adrenergic receptor blocking agent; digoxin; dipeptidyl carboxypeptidase inhibitor; diuretic agent; sotalol; adolescent; adult; article; atrioventricular septal defect; body mass; cardiopulmonary exercise test; cavopulmonary connection; child; controlled study; female; Fontan procedure; heart atrium overload; heart function; heart right ventricle double outlet; heart single ventricle; heart ventricle overload; human; hypoplastic left heart syndrome; lung ventilation; major clinical study; male; oxygen consumption; preschool child; protein secretion; rest; right heart hypoplasia; school child; tricuspid valve atresia

Fluid-structure interaction simulations of the Fontan procedure using variable wall properties - Long, C.C.; Hsu, M.-C.; Bazilevs, Y.; Feinstein, J.A.; Marsden, A.L. (International journal for numerical methods in biomedical engineering, 2012)
Children born with single ventricle heart defects typically undergo a staged surgical procedure culminating in a total cavopulmonary connection (TCPC) or Fontan surgery. The goal of this work was to perform physiologic, patient-specific hemodynamic simulations of two post-operative TCPC patients by using fluid-structure interaction (FSI) simulations. Data from two patients are presented, and post-op anatomy is reconstructed from MRI data. Respiration rate, heart rate, and venous pressures are obtained from catheterization data, and inflow rates are obtained from phase contrast MRI data and are used together with a respiratory model. Lumped parameter (Windkessel) boundary conditions are used at the outlets. We perform FSI simulations by using an arbitrary Lagrangian-Eulerian finite element framework to account for motion of the blood vessel walls in the TCPC. This study is the first to introduce variable elastic properties for the different areas of the TCPC, including a Gore-Tex conduit. Quantities such as wall shear stresses and pressures at critical locations are extracted from the simulation and are compared with pressure tracings from clinical data as well as with rigid wall simulations. Hepatic flow distribution and energy efficiency are also calculated and compared for all cases. There is little effect of FSI on pressure tracings, hepatic flow distribution, and time-averaged energy efficiency. However, the effect of FSI on wall shear stress, instantaneous energy efficiency, and wall motion is significant and should be considered in future work, particularly for accurate prediction of thrombus formation.
Keywords: biological model; biomechanics; child; computer simulation; female; finite element analysis; Fontan procedure; congenital heart malformation; hemodynamics; human; male; mechanical stress; pathology; pathophysiology; physiology; preschool child; pressure

Severe cyanosis after kawashima operation resulting from congenital portosystemic shunt - Nakamura, Y.; Aoki, M.; Hagino, I.; Nakajima, H. (Annals of Thoracic Surgery, 2012)
We describe an unusual case of a patient with polysplenia, inferior vena cava (IVC) interruption, and unrecognized congenital portosystemic venous connection (CPVC) in whom severe cyanosis developed in the acute postoperative stage after a Kawashima operation and required urgent surgical division of the CPVC. It has been stressed recently that CPVCs and other abdominal venous abnormalities have been underdiagnosed in patients with polysplenia and IVC interruption, and we think that a routine evaluation of abdominal venous connections should be mandatory before considering the Kawashima operation for these patients. © 2012 The Society of Thoracic Surgeons.
Keywords: contrast medium; nitric oxide; accessory spleen; ambient air; arterial oxygen saturation; article; case report; central venous pressure; computer assisted tomography; congenital portosystemic shunt; contrast enhancement; cyanosis; disease severity; echocardiography; Fontan procedure; heart atrium pressure; heart catheterization; heart left right shunt; heart right ventricle double outlet; liver vein; human; infant; inferior cava vein; internal jugular vein; Kawashima operation; kidney vein; laparotomy; lung artery pressure; lung blood flow; male; newborn; postoperative period; priority journal; pulmonary valve stenosis; splenic vein; superior cava vein; surgical technique; thorax surgery

Bupropion: Congenital heart defects (continued) (Prescrire International, 2012)
• Bupropion, an amphetamine, is authorised as an aid to smoking cessation, despite its negative harm-benefit balance. • In 2004, data from a registry of pregnancies exposed to bupropion drew attention to an increased risk of congenital heart defects. • In 2010, a case-control study including more than 10 000 children showed a higher incidence of in utero exposure to bupropion among children who had congenital left heart defects. Other, less reliable studies did not show such a link. • In practice, this risk of congenital heart defects is yet another reason to avoid using bupropion, including during pregnancy, and to monitor the cardiac status of exposed fetuses and newborns. ©Prescrire.
Keywords: amfebutamone; aortic coarctation; aortic stenosis; congenital malformation; congenital heart malformation; human; hypoplastic left heart syndrome; patient monitoring; patient safety; pregnancy; short survey; smoking cessation; teratogenicity

Bupropion: Congenital heart defects (Prescrire International, 2012)
• Bupropion, an amphetamine, is authorised as an aid to smoking cessation, despite its negative harm-benefit balance. • In 2004, data from a registry of pregnancies exposed to bupropion drew attention to an increased risk of congenital heart defects. • In 2010, a case-control study including more than 10 000 children showed a higher incidence of in utero exposure to bupropion among children who had congenital left heart defects. Other, less reliable studies did not show such a link. • In practice, this risk of congenital heart defects is yet another reason to avoid using bupropion, including during pregnancy, and to monitor the cardiac status of exposed fetuses and newborns. ©Prescrire.
Keywords: amfebutamone; amphetamine derivative; serotonin uptake inhibitor; aortic coarctation; aortic stenosis; article; cardiovascular risk; congenital heart disease; congenital heart malformation; drug exposure; drug safety; drug traffic; fetus monitoring; human; hypoplastic left heart syndrome; patient safety; prenatal exposure; smoking cessation; tobacco dependence

Cardiovascular abnormalities in Down's syndrome: Spectrum, management and survival over 22 years - Irving, C.A.; Chaudhari, M.P. (Archives of Disease in Childhood, 2012)
Background: The prevalence of cardiovascular anomalies in Down's syndrome is well described, but there are few data on spectrum, management and outcome. The authors aimed to provide this information for infants with Down's syndrome in a defined population over a 22-year period. Methods: The regional paediatric cardiology database in Newcastle upon Tyne provided information on all cardiovascular anomalies, surgical treatment and outcome. Data was subdivided into two eras, 1985-1995 and 1996-2006, and surgical results and outcomes compared. Data on live births with Down's syndrome were obtained from the Northern Congenital Abnormality Survey (NorCAS). Denominator data on all live births in the region were obtained from UK Statistics. Results: In 1985-2006 there were 754,486 live births in the population. 821 infants were live-born with Down's syndrome (1.09 per 1000 live births). 342 (42%) infants with Down's syndrome had a cardiovascular anomaly. The commonest anomaly was complete atrioventricular septal defect in 125 (37%) infants. Three patients had univentricular physiology. In 1985-1995, 101/163 (62%) infants had surgery with 30% mortality; in 1996-2006, 129/180 (72%) had surgery with 5% mortality. One patient underwent Fontan completion. There were two cardiac transplants for cardiomyopathy. One-year survival in Down's syndrome with a cardiovascular anomaly improved from 82% in 1985-1995 to 94% in 1996-2006. Conclusions: The incidence of cardiovascular anomalies in Down's syndrome was 42%. There has been a significant reduction in postoperative mortality and improvement in 1-year survival. Treatment modalities such as single ventricle palliation and cardiac transplantation are now considered in these patients.
Keywords: article; cardiovascular malformation; congestive cardiomyopathy; disease association; Down syndrome; heart atrium septum defect; heart transplantation; heart ventricle septum defect; human; infant; live birth; major clinical study; mortality; patent ductus arteriosus; prevalence; priority journal; survival time

Perioperative plasma F2-isoprostane levels correlate with markers of impaired ventilation in infants with single-ventricle physiology undergoing stage 2 surgical palliation on the cardiopulmonary bypass - Albers, E.; Donahue, B.S.; Milne, G.; Saville, B.R.; Wang, W.; Bichell, D.; McLaughlin, B. (Pediatric Cardiology, 2012)
Cardiopulmonary bypass (CPB) produces inflammation and oxidative stress, which contribute to postoperative complications after cardiac surgery. F 2-Isoprostanes (F2-IsoPs) are products of lipid oxidative injury and represent the most accurate markers of oxidative stress. In adults undergoing cardiac surgery, CPB is associated with elevated IsoPs. The relationship between F2-IsoPs and perioperative end-organ function in infants with singleventricle physiology, however, has not been well studied. This study prospectively enrolled 20 infants (ages 3-12 months) with univentricular physiology undergoing elective stage 2 palliation (bidirectional cavopulmonary anastomosis). Blood samples were collected before the surgical incision (T0), 30 min after initiation of CPB (T1), immediately after separation from CPB (T2), and 24 h postoperatively (T3). Plasma F2-IsoP levels were measured at each time point and correlated with indices of pulmonary function and other relevant clinical variables. Plasma F2-IsoPs increased significantly during surgery, with highest levels seen immediately after separation from CPB (p<0.001). After separation from CPB, increased F2-IsoP was associated with lower arterial pH (ρ = -0.564; p = 0.012), higher partial pressure of carbon dioxide (PaCO2; ρ = 0.633; p = 0.004), and decreased lung compliance (ρ = -0.783; p ≤ 0.001). After CPB, F2-IsoPs did not correlate with duration of CPB, arterial lactate, or immediate postoperative outcomes. In infants with singleventricle physiology, CPB produces oxidative stress, as quantified by elevated F 2-IsoP levels. Increased F2-IsoP levels correlated with impaired ventilation in the postoperative period. The extent to which F 2-IsoPs and other bioactive products of lipid oxidative injury might predict or contribute to organ-specific stress warrants further investigation. © Springer Science+Business Media, LLC 2012.
Keywords: biological marker; carbon dioxide; isoprostane derivative; article; bidirectional cavopulmonary anastomosis; blood sampling; cardiopulmonary bypass; cavopulmonary connection; clinical article; concentration (parameter); disease marker; female; heart single ventricle; human; infant; lung compliance; lung function; lung injury; lung perfusion; male; outcome assessment; oxidative stress; palliative therapy; perioperative period; pulmonary dysfunction; reoperation

Patients with univentricular heart in early childhood: Parenting stress and child behaviour - Sarajuuri, A.; Lönnqvist, T.; Schmitt, F.; Almqvist, F.; Jokinen, E. (Acta Paediatrica, International Journal of Paediatrics, 2012)
Aims: To assess perceptions of child behaviour and parenting stress among the parents of young children with hypoplastic left heart syndrome (HLHS) and other forms of functionally univentricular heart defects (UVH). Methods: As part of our prospective nation-wide neurodevelopmental follow-up study, the parents of 23 patients with HLHS, 14 with UVH and 46 healthy controls at the mean age of 18 months received the questionnaires Child Behavior Checklist and Parenting Stress Index. Results: The reported level of total parenting stress was significantly higher among the mothers (mean score 241 vs 205, p < 0.001) and fathers (235 vs 202, p = 0.003) of patients with HLHS compared with those of controls. The parents of patients with HLHS reported significantly more total (mean T score 52 vs 45, p = 0.005) and internalizing (51 vs 41, p < 0.001) behaviour problems than the controls, but among the syndrome scales, a significant difference was only found in somatic complaints. The parents of patients with UVH did not report more parenting stress or emotional problems than the controls. Conclusion: Hypoplastic left heart syndrome, a severe congenital heart defect, increases parenting stress. The reported emotional maladjustment in affected children might in part be owing to somatic complaints. © 2011 The Author(s)/Acta Pædiatrica © 2011 Foundation Acta Pædiatrica.
Keywords: article; child; child behavior; Child Behavior Checklist; clinical article; comparative study; controlled study; emotional disorder; female; follow up; heart single ventricle; human; hypoplastic left heart syndrome; male; outcome assessment; parental stress; preschool child; priority journal; prospective study; scoring system; self concept

Minor symptoms of depression in patients with congenital heart disease have a larger impact on quality of life than limited exercise capacity - Müller, J.; Hess, J.; Hager, A. (International Journal of Cardiology, 2012)
Objective: In patients with congenital heart disease quality of life is only marginally associated with exercise capacity. The aim of this study was to determine the prevalence of depression and its impact on quality of life and exercise capacity. Patients and methods: From November 2007 to October 2009 a total of 767 patients (352 female, 14-67 years) with various congenital heart diseases (37 palliated/native cyanotic, 57 Fontan, 74 Transposition of the Great Arteries (TGA) after atrial switch, 50 other TGA, 136 Fallot, 38 Ebstein, 47 Pulmonic stenosis/regurgitation, 68 aortic coarctation, 103 aortic stenosis, 90 isolated shunts, 67 other) completed the health-related quality of life questionnaire SF-36 and the German translation of the "Center for Epidemiologic Studies Depression Scale" (CES-D) to assess depressive symptoms. Afterwards a cardiopulmonary exercise test was performed. Results: Only 66 patients (8.6%) showed depressive symptoms fulfilling the CES-D definition for depression. The total prevalence of depression was lower than in the general population (Wilcoxon test, p < 0.001) and did not differ substantially in between the diagnostic subgroups (Kruskal-Wallis test, p = 0.195). CES-D score was correlated to all of the nine dimensions of quality of life (r = -0.170 to r = -0.740, p < 0.001) and less pronounced to exercise capacity (r = -0.164, p < 0.001). Correlation of peak oxygen uptake to quality of life was weaker than the CES-D scores in all subscales of life quality. Conclusions: Patients with congenital heart disease are rarely depressive. However, even minor depressive symptoms have a stronger impact on quality of life than limited exercise capacity as seen in many patients. © 2011 Published by Elsevier Ireland Ltd.
Keywords: adolescent; adult; aged; aortic coarctation; aortic stenosis; article; clinical assessment; clinical feature; cohort analysis; congenital heart disease; controlled study; cyanotic heart disease; depression; disease association; Ebstein anomaly; exercise; Fallot tetralogy; female; great vessels transposition; heart septum defect; human; major clinical study; male; oxygen consumption; population research; prevalence; priority journal; pulmonary valve insufficiency; pulmonary valve stenosis; quality of life; scoring system

The process of family management when a baby is diagnosed with a lethal congenital condition. - Rempel, G.R.; Blythe, C.; Rogers, L.G.; Ravindran, V. (Journal of family nursing, 2012)
The Family Management Style Framework (FMSF) was used as a conceptual basis for secondary data analysis of 55 previously conducted interviews with mothers and fathers of children with a lethal congenital condition from two surgical treatment eras. The directed content analysis was guided by a coding structure developed from family management dimensions identified in prior research of family response to childhood chronic conditions. Results indicated that application of the FMSF was helpful in differentiating families and their processes of family management at the onset of their infant's illness through to surviving the first surgery and going home. The dimensions of Illness View and Child Identity were central to the parents' capacity to manage their baby's illness demands within their family context. Applying a robust family framework to a complex neonatal condition at illness onset provides compelling direction for clinical interventions and their rigorous evaluation.
Keywords: adaptive behavior; adult; article; Canada; caregiver; comparative study; decision making; female; heart surgery; human; hypoplastic left heart syndrome; interview; male; middle aged; newborn; Norwood procedure; palliative therapy; parent; psychological aspect; psychological model

Essentials of paediatric cardiac surgery - Barron, D.J.; Jones, T.J.; Mussa, S. (Surgery, 2012)
The history of cardiac surgery began with procedures to treat congenital heart disease, from the Blalock-Taussig shunt in the 1940s to the first use of extra-corporeal circulation in the 1950s. The whole speciality of cardiothoracic surgery has grown from the work of these early pioneers and the wider applications of cardio-pulmonary bypass have led to surgery for coronary artery disease and degenerative valvular disease in adults. Surgery for congenital heart disease now accounts for 10-15% of all cardiac surgery and continues to be at the forefront of the speciality in terms of innovation and evolving approaches. The speciality has advanced in parallel with advances in neonatal medicine and paediatric intensive care that have enabled an increasingly more complex range of conditions to become treatable. Outcomes have steadily improved, although this remains one of the most high-risk areas of modern surgery. Major congenital heart disease is a very serious condition and only 15% of children survived infancy prior to the surgical era. Now over 85% of children survive into adulthood and, for the first time, there are now more adults alive with congenital heart disease than there are children. Caring for these patients has led to the development of 'adult congenital heart disease' as an emerging specialist area. Surgery has become increasingly specialized and technically demanding with a trend to repair lesions at an earlier age and to aim for complete anatomical repair in infancy rather than a series of staged procedures. Over two-thirds of all procedures are now carried out before the age of 1 year.
Keywords: immunosuppressive agent; adulthood; aortic coarctation; aortic stenosis; article; atrioventricular septal defect; Blalock Taussig shunt; cardiac graft rejection; cardiopulmonary bypass; child; congenital heart disease; coronary artery disease; extracorporeal circulation; Fallot tetralogy; great vessels transposition; heart atrium septum defect; heart catheterization; heart failure; heart right ventricle double outlet; heart septum defect; heart surgery; heart transplantation; heart ventricle septum defect; high risk patient; human; hypoplastic left heart syndrome; immunosuppressive treatment; incidence; infancy; intensive care; interventional cardiovascular procedure; lung circulation; medical specialist; open heart surgery; patent ductus arteriosus; pediatric surgery; pediatrics; priority journal; pulmonary valve stenosis; quality of life; surgical anatomy; surgical approach; surgical technique; survival rate; thorax surgery; treatment planning; tricuspid valve atresia

ST segment depression following pulmonary artery banding - Retnamma, R.K.; Nair, S.G.; Sunil, G.S.; Benedict, R. (Annals of Cardiac Anaesthesia, 2012)
Keywords: epinephrine; glyceryl trinitrate; artery compression; article; artificial ventilation; case report; clinical feature; coronary artery compression; human; hypoplastic left heart syndrome; infant; intensive care unit; lung artery banding; mitral valve atresia; outcome assessment; oxygen saturation; patent foramen ovale; ST segment depression; tachycardia

Independent risk factors for cardiac operations in adults with congenital heart disease: A retrospective study of 543 operations for 500 patients - Vogt, M.O.; Hörer, J.; Grünewald, S.; Otto, D.; Kaemmerer, H.; Schreiber, C.; Hess, J. (Pediatric Cardiology, 2012)
Adults with congenital heart disease (CHD) are an increasing population requiring cardiac operations. To date, the perioperative risk factors for this group have not been identified. This study aimed to identify clinical, morphologic, and hemodynamic risk factors for an adverse outcome. This study retrospectively analyzed a cohort of 500 patients (ages[16 years) who underwent 543 operations between January 2004 and December 2008 at a single center. The composite end point of an adverse outcome was in-hospital death, a prolonged intensive care exceeding 4 days, or both. The composite end point was reached by 253 of the patients (50.6%). Of the 500 patients, 13 (2.6%) died within 30 days after the operation. After logistic regression analysis, the following eight items remained significant: male gender (P = 0.003; odds ratio [OR] 1.8; 95% confidence interval [CI] 1.2-2.6), cyanosis (P > 0.006; OR 3.7; 95% CI 1.5-9.4), functional class exceeding 2 (P = 0.004; OR 2.2; 95% CI 1.3-3.7), chromosomal abnormalities (P = 0.004; OR 3.3; 95% CI 1.4-7.7), impaired renal function (P = 0.019; OR 3.8; 95% CI 1.2-11.5), systemic right ventricle (RV) in a biventricular circulation (P = 0.027; OR 3.3; 95% CI 1.1-9.5), enlargement of the systemic ventricle (P = 0.011; OR 1.7; 95% CI 1.1-2.6), and operation with extracorporeal circulation (P = 0.002; OR 4.3; 95% CI 1.7-11.4). Early mortality in the current adult CHD population is low. Morbidity, however, is significant and influenced by the patients' conditions (male gender, chromosomal abnormalities), history (cyanosis, New York Hospital Association [NYHA] class), and underlying morphology (systemic RV). This information for a large cohort of patients could help progress toward more adequate counseling for adults with a congenital heart defect. © Springer Science+Business Media, LLC 2011.
Keywords: liver enzyme; adolescent; adult; adverse outcome; aged; article; assisted circulation; body mass; chromosome aberration; cohort analysis; congenital heart disease; cyanosis; diabetes mellitus; DiGeorge syndrome; disease classification; Down syndrome; endocarditis; enzyme blood level; female; functional status; glomerulus filtration rate; heart arrhythmia; heart hemodynamics; heart right ventricle; heart single ventricle; heart surgery; human; hypertension; hyperthyroidism; hyponatremia; hypothyroidism; intubation; kidney dysfunction; major clinical study; male; Marfan syndrome; neurologic disease; outcome assessment; pericardial effusion; pleura effusion; polycythemia; postoperative complication; postoperative hemorrhage; postoperative infection; reoperation; retrospective study; sex difference; surgical mortality; surgical risk; tracheotomy

Hemodynamic simulation for surgical treatment of congenital heart disease. - Qian, Y.; Liu, J.L.; Liu, J.F. (Conference proceedings : ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Conference, 2012)
Numerical analysis of cardiovascular flow is one of several methods of use for the quantitative evaluation of patient-specific treatments. However, due to the complexity of vascular geometry and flow conditions, the cardiovascular flow simulation continues to be a challenging project. As the flow at the peak of systolic heart beat displayed full turbulence, the congenital heart treatments, Norwood and TCPC procedure, were investigated through the use of computational hemodynamic technology, in the present study. On the other hand, at diastolic period, the flow fell to an almost sedentary state. This indicated that the cardiovascular flow experienced a strange transition of flow from systolic peak to diastole. Thus, in order to accurately simulate this transitional flow, a very small time step was applied in the k - ε turbulent model calculation. Energy losses (EL), local pressure and wall shear stress were analyzed to estimate the result of clinical treatments. It was found that the value of EL, including the influence of respiration, was 1.5 times higher than the value of EL, disregarding respiratory influences. These results indicated that the hemodynamic outcomes of TCPC treatment are noticeably influenced by respiration. The effect of respiration plays an important role in estimating the results of TCPC treatment and thus should be included as one of the important conditions of computational hemodynamic analysis.
Keywords: article; biological model; computer assisted surgery; computer simulation; coronary artery blood flow; Fontan procedure; hemodynamics; human; hypoplastic left heart syndrome; infant; newborn; Norwood procedure; pathology; pathophysiology; statistics; three-dimensional imaging

Perspectives in ablation of arrhythmias in children and patients with congenital heart disease - Pflaumer, A. (Internal Medicine Journal, 2012)
Although most arrhythmias in children have a benign outcome, recurrent arrhythmic events have a significant impact on quality of life. Electrophysiology studies with ablation have good short-term success and an acceptably low complication rate. The long-term outlook for this patient group is incompletely defined, however. Factors that require special consideration in children include the need to limit the size, depth and number of lesions, and the radiation exposure incurred during fluoroscopy-guided catheters manipulation. The use of cryoablation seems promising in limiting lesion size. Three-dimensional (3D) mapping systems clearly have been shown to reduce the radiation dose. In congenital heart disease, these advances in technology have helped to further our understanding of the mechanisms underlying arrhythmias. It is anticipated that earlier intervention and newer operative techniques will reduce the incidence of postoperative arrhythmias in the future. For those patients who still develop tachyarrythmias after cardiac surgery, the use of three-dimensional systems and other new technologies permits more efficient intervention in the electrophysiology laboratory.
Keywords: article; atrial switch operation; atrioventricular nodal reentry tachycardia; catheter ablation; child; computer assisted tomography; congenital heart disease; coronary artery obstruction; cryoablation; electrophysiology; fluoroscopy; Fontan procedure; guiding catheter; heart arrhythmia; heart atrium flutter; heart surgery; human; invasive procedure; nuclear magnetic resonance imaging; paroxysmal supraventricular tachycardia; postoperative complication; priority journal; radiation dose; radiation exposure; supraventricular tachycardia; surgical technique; tachycardia induced cardiomyopathy; three-dimensional imaging

Three-dimensional simulations in glenn patients: Clinically based boundary conditions, hemodynamic results and sensitivity to input data - Troianowski, G.; Taylor, C.A.; Feinstein, J.A.; Vignon-Clementel, I.E. (Journal of Biomechanical Engineering, 2011)
While many congenital heart defects can be treated without significant long term sequelae, some achieve successful palliation as their definitive endpoints. The single-ventricle defect is one such defect and leaves the child with only one operational ventricle, requiring the systemic and the pulmonary circulations to be placed in series through several operations performed during early childhood. Numerical simulations may be used to investigate these hemodynamic conditions and their relation to post-operative sequelae; however, they rely heavily on boundary condition prescription. In this study, we investigate the impact of hemodynamic input data uncertainties on simulation results. Imaged-based patient-specific models of the multi-branched pulmonary arteries and superior vena cava were built for five cavopulmonary connection (i.e. Glenn) patients. Magnetic resonance imaging and catheterization data were acquired for each patient prior to their Fontan surgery. Inflow and outflow boundary conditions were constructed to match available clinical data and resulted in the development of a framework to incorporate these types of clinical data into patient-specific simulations. Three-dimensional computational fluid dynamics simulations were run and hemodynamic indicators were computed. Power loss was low (and efficiency very high) and a linear correlation was found between power loss and cardiac index among the five patients. Other indicators such as low wall shear stress were considered to better characterize these patients. Flow was complex and oscillatory near the anastomosis, and laminar in the smaller branches. While common trends were seen among patients, results showed differences among patients, especially in the 3D maps, strengthening the importance of patient-specific simulations. A sensitivity analysis was performed to investigate the impact of input data (clinical and modeling) to construct boundary conditions on several indicators. Overall, the sensitivity of the output indicators to the input data was small but non-negligible. The sensitivity of commonly used hemodynamic indicators to compare patients is discussed in this context. Power efficiency was much more sensitive to pressure variation than power loss. To increase the precision of such indicators, mean flow split between right and left lungs needs to be measured with more accuracy with higher priority than refining the model of how the flow is distributed on average among the smaller branches. Although ± 10 % flow split imprecision seemed reasonable in terms of patient comparison, this study suggests that the common practice of imposing a right pulmonary artery/left pulmonary artery flow split of 55 %/45 % when performing patient specific simulations should be avoided. This study constitutes a first step towards understanding the hemodynamic differences between pre-and post Fontan surgery, predicting these differences, and evaluating surgical outcomes based on preoperative data. © 2011 American Society of Mechanical Engineers.
Keywords: anastomosis; artery blood flow; article; catheterization; child; computational fluid dynamics; Fontan procedure; Glenn shunt; cardiac index; hemodynamics; human; laminar flow; lung blood flow; nuclear magnetic resonance imaging; oscillatory potential; outcome assessment; power analysis; preschool child; pressure; pulmonary artery; sensitivity analysis; shear stress; simulation; superior cava vein; three-dimensional imaging

Adult congenital surgery: Current management - Vouhé, P.R. (Seminars in Thoracic and Cardiovascular Surgery, 2011)
The population of adults with congenital heart disease (CHD) (commonly called grown-ups with congenital heart disease or GUCH) is increasing steadily and exceeds the population of children with CHD already. The specificities of GUCH surgery are multiple and include (1) variety of the anatomo-clinical situations (defects repaired during childhood, malformations either nonoperated or palliated, nonreparable defects), (2) usual multiorgan involvement, and (3) many technical differences related to cardiopulmonary bypass, myocardial protection, and surgical technique. The surgical indications should be taken after a precise evaluation of the risk/benefit ratio on an individual basis; a balanced attitude should be kept between unwise interventionism and excessive waiting policy. It is now agreed that GUCH surgery should be performed in specialized centers with large patient volumes and expertise of both surgical and medical disciplines. Much remains to be done to implement these recommendations and to accumulate experience and evidence-based information to provide optimal outcome. © 2011 Elsevier Inc.
Keywords: antiarrhythmic agent; anticoagulant agent; antithrombocytic agent; blood clotting factor; erythropoietin; fresh frozen plasma; heparin; adult congenital heart surgery; air embolism; aortic clamping; article; biventricular malformation; bleeding; blood vessel occlusion; cardiac graft rejection; cardiopulmonary bypass; cerebrovascular accident; chromosome disorder; clinical competence; clinical decision making; comorbidity; computer assisted tomography; congenital heart disease; conservative treatment; coronary artery disease; cyanosis; echocardiography; embolism; evidence based medicine; Fontan procedure; functional status; graft failure; grown ups with congenital heart disease; heart catheterization; heart disease; heart muscle fibrosis; heart protection; heart surgery; heart transplantation; heart ventricle hypertrophy; human; long term care; lung blood vessel; lung vascular resistance; nuclear magnetic resonance imaging; palliative therapy; phlebotomy; plasma transfusion; postoperative complication; postoperative hemorrhage; prognosis; prosthesis; pulmonary vascular disease; quality of life; recurrent disease; reoperation; risk benefit analysis; risk factor; silent myocardial ischemia; sternotomy; surgical training; survival rate; teamwork; thoracotomy; thrombocyte transfusion; treatment indication; ultrafiltration; vascular access

New concepts: Development of a survivorship programme for patients with a functionally univentricular heart - Goldberg, D.J.; Dodds, K.; Rychik, J. (Cardiology in the Young, 2011)
Children with functionally univentricular hearts are now surviving into their third and fourth decades of life. Although survival alone is a remarkable achievement, a lot must still be done to improve the quality and duration of life after the Fontan operation. Challenges that may be faced by these patients include the impact of the Fontan operation on the liver and the density of bone, protein-losing enteropathy, and plastic bronchitis. Paediatric cardiologists are familiar with the haemodynamic issues inherent in Fontan physiology; however, training in cardiology is often not sufficient to give us a complete understanding of the pathophysiology of the complications or of the options for treatment. Collaboration with other subspecialists including gastroenterologists, endocrinologists, and pulmonologists is essential in order to provide the rigorous and nuanced care that our patients need and deserve. A clinic in which a patient can see multiple subspecialists, and in which the subspecialists, as a group, can discuss each patient, can provide a unique and valuable service for patients with a functionally univentricular heart. © 2011 Cambridge University Press.
Keywords: article; bone density; bronchitis; croupous bronchitis; Fontan procedure; heart single ventricle; human; liver cirrhosis; patient care; protein losing gastroenteropathy; quality of life

Changing attitudes to the management of hypoplastic left heart syndrome: A European perspective - Murtuza, B.; Elliott, M.J. (Cardiology in the Young, 2011)
Background and aims Several years ago, one of us described the difference in attitude to patients with hypoplastic left heart syndrome in the United States of America and Europe as similar to that between Mars and Venus. Uncertainty remains with regard to the long-term prognosis for patients with hypoplastic left heart syndrome. This prognosis may be considered in terms of survival, functional performance, including exercise capacity and neurodevelopment, as well as psychosocial effects on the patient, family, and siblings. Counselling parents where either an antenatal or postnatal diagnosis of hypoplastic left heart syndrome has been made requires practitioners to give information on these prognostic aspects. We wanted to see how attitudes among European surgeons have changed over the last few years.Methods We performed a review of recent European data for hypoplastic left heart syndrome and conducted a survey among surgeons in major European centres to ascertain key aspects of their attitudes to the management of patients with hypoplastic left heart syndrome and how they counsel parents.Results and conclusions As of January, 2011, 2392 citations in the PubMed database were available for the search string "hypoplastic left heart". The majority of these were from the centres from the United States of America and Europe. The European Association for Cardio-Thoracic Surgery Congenital Heart Surgery Database shows an annual increase in the number of Norwood (Stage I) operations for hypoplastic left heart syndrome from 2003 to 2009, with a corresponding reduction in mortality. European rates of antenatal detection vary widely between centres, as do the rates of termination for a prenatal diagnosis of hypoplastic left heart syndrome. We observed a wide variation in the estimates of surgeons for survival and quality of life for surgical palliation of hypoplastic left heart syndrome, as well as in their estimates for actual rates of termination of pregnancy in their centres. Further, there was marked inconsistency in the information given to parents as part of the process of counselling. These issues remain to be resolved if parents are to make a fully informed decision for their child. © 2011 Cambridge University Press.
Keywords: article; controlled study; exercise; family counseling; functional assessment; heart performance; human; hypoplastic left heart syndrome; mental development; Norwood procedure; patient care; patient information; physician attitude; pregnancy termination; prenatal diagnosis; professional practice; prognosis; psychosocial care; quality of life; surgical mortality; survival rate; survival time

Thrombolysis with rt-PA for an ischemic stroke in boy treated with Fontan operation - Bianco, M.; Simionato, F.; Giusti, C.; Corea, F.; Giua, A.; Martinelli, V.; Comi, G.; Sessa, M. (Journal of Pediatric Neurology, 2011)
We first report the case of a 14-year-old boy, previously treated with a modified Fontan operation at the age of 2, who underwent an intra-arterial thrombolysis for an ischemic stroke with a favorable outcome. No controlled randomized trials on thrombolysis among childhood stroke have been conducted yet. This and other similar cases suggest that thrombolysis may also be safe and beneficial in pediatric patients and those cases may benefit from a prompt access to specialized stroke centers. © 2011-IOS Press and the authors. All rights reserved.
Keywords: alteplase; adolescent; article; ataxic aphasia; blood clot lysis; brain ischemia; case report; Caucasian; cavopulmonary connection; child; computer assisted tomography; Fontan procedure; general anesthesia; hemiparesis; hemiplegia; human; Italy; magnetic resonance angiography; male; middle cerebral artery occlusion; preschool child

Coming from behind to win--a qualitative research about psychological conditions of adolescents who have undergone open-heart surgery for single ventricle between the ages 0-5. - Zahmacioglu, O.; Yildiz, C.E.; Koca, B.; Ugurlucan, M.; Gokalp, S.; Cetin, G.; Eroglu, A.G.; Oztunc, F. (Journal of cardiothoracic surgery, 2011)
Early recognition of congenital cardiac pathologies and their treatment by means of palliative or corrective surgery at birth or infancy has vital importance. Successful repair of congenital cardiac defects by surgical methods has gained importance especially during the last twenty years. As the scope of the surveillance increased so did the interest in the outcomes of these treatments when the patients had reached puberty and adulthood. The purpose of our research was to study the psychological framework of the adolescents who had experienced these surgeries by listening both the children and the parents talk about their feelings and experiences. Our data was accumulated through interviews with 17 adolescents and their families, using qualitative methods. The main theme at the end of the analysis was "to be strong and resistive". We reached the conclusion that this condition was not a pathological build up but an attitude of coping, as it did not cause loss of functionality. The defensive psychological mechanisms used by these adolescents consisted of repression, compensation and reaction formation. We believe that this information is important to understand the real meaning of the manners displayed when these adolescents and their families pursue their daily lives, communicate and make relationships with their environment and especially professionals in the health services.
Keywords: adaptive behavior; adolescent; article; comparative study; congenital heart malformation; congenital malformation; female; heart surgery; heart ventricle; human; infant; male; newborn; preschool child; psychological aspect; qualitative research; questionnaire

Norwood with right ventricle-to-pulmonary artery conduit is more effective than Norwood with Blalock-Taussig shunt for hypoplastic left heart syndrome: Mathematic modeling of hemodynamics - Mroczek, T.; Małota, Z.; Wójcik, E.; Nawrat, Z.; Skalski, J. (European Journal of Cardio-thoracic Surgery, 2011)
Objective: The introduction of right ventricle to pulmonary artery (RV-PA) conduit in the Norwood procedure for hypoplastic left heart syndrome resulted in a higher survival rate in many centers. A higher diastolic aortic pressure and a higher mean coronary perfusion pressure were suggested as the hemodynamic advantage of this source of pulmonary blood flow. The main objective of this study was the comparison of two models of Norwood physiology with different types of pulmonary blood flow sources and their hemodynamics. Method: Based on anatomic details obtained from echocardiographic assessment and angiographic studies, two three-dimensional computer models of post-Norwood physiology were developed. The finite-element method was applied for computational hemodynamic simulations. Norwood physiology with RV-PA 5-mm conduit and Blalock-Taussig shunt (BTS) 3.5-mm shunt were compared. Right ventricle work, wall stress, flow velocity, shear rate stress, energy loss and turbulence eddy dissipation were analyzed in both models. Results: The total work of the right ventricle after Norwood procedure with the 5-mm RV-PA conduit was lower in comparison to the 3.5-mm BTS while establishing an identical systemic blood flow. The Qp/Qs ratio was higher in the BTS group. Conclusions: Hemodynamic performance after Norwood with the RV-PA conduit is more effective than after Norwood with BTS. Computer simulations of complicated hemodynamics after the Norwood procedure could be helpful in establishing optimal post-Norwood physiology. © 2011 European Association for Cardio-Thoracic Surgery.
Keywords: angiography; article; biological model; Blalock Taussig shunt; blood pressure measurement; computer simulation; controlled study; Doppler flowmetry; echocardiography; flow rate; heart cycle; heart hemodynamics; heart right ventricle; heart right ventricle pressure; human; hypoplastic left heart syndrome; intermethod comparison; lung blood flow; major clinical study; newborn; Norwood procedure; priority journal; right ventricle to pulmonary artery conduit; shear stress; systemic circulation; systole; wall stress

Relation of milrinone after surgery for congenital heart disease to significant postoperative tachyarrhythmias - Smith, A.H.; Owen, J.; Borgman, K.Y.; Fish, F.A.; Kannankeril, P.J. (American Journal of Cardiology, 2011)
Milrinone reduces the risk of low cardiac output syndrome for some pediatric patients after congenital heart surgery. Data from adults undergoing cardiac surgery suggest an association between milrinone and an increased risk of postoperative arrhythmias. We tested the hypothesis that milrinone is an independent risk factor for tachyarrhythmias after congenital heart surgery. Subjects undergoing congenital heart surgery at our institution were consecutively enrolled for 38 months, through September 2010. The data were prospectively collected, including a review of full-disclosure telemetry and the medical records. Within 38 months, 603 enrolled subjects underwent 724 operative procedures. The median age was 5.5 months (range 0.0 to 426), the median weight was 6.0 kg (range 0.7 to 108), and the cohort was 45% female. The overall arrhythmia incidence was 50%, most commonly monomorphic ventricular tachycardia (n = 85, 12%), junctional ectopic tachycardia (n = 69, 10%), accelerated junctional rhythm (n = 58, 8%), and atrial tachyarrhythmias (including atrial fibrillation, atrial flutter, and ectopic or chaotic atrial tachycardia, n = 58, 8%). Multivariate logistic regression analysis demonstrated that independent of age <1 month, the use of cardiopulmonary bypass, the duration of cardiopulmonary bypass, Risk Adjusted classification for Congenital Heart Surgery, version 1, score >3, and the use of epinephrine or dopamine, milrinone use on admission to the cardiac intensive care unit remained independently associated with an increase in the odds of postoperative tachyarrhythmia resulting in an intervention (odds ratio 2.8, 95% confidence interval 1.3 to 6.0, p = 0.007). In conclusion, milrinone use is an independent risk factor for clinically significant tachyarrhythmias in the early postoperative period after congenital heart surgery. © 2011 Elsevier Inc. All rights reserved.
Keywords: adenosine; epinephrine; amiodarone; dopamine; milrinone; aortic coarctation; article; cardiopulmonary bypass; cardiovascular risk; cardioversion; child; clinical classification; cohort analysis; congenital heart disease; continuous infusion; controlled study; disease association; Fallot tetralogy; female; forward heart failure; heart arrhythmia; heart atrium arrhythmia; atrial fibrillation; heart atrium flutter; heart atrium septum defect; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; incidence; infant; intensive care unit; loading drug dose; major clinical study; male; monomorphic ventricular tachycardia; postoperative period; preschool child; priority journal; prospective study; risk assessment; risk reduction; scoring system; supraventricular tachycardia; tachycardia; telemetry; treatment duration

Measures of exercise capacity in adults with congenital heart disease - Buys, R.; Cornelissen, V.; De Bruaene, A.V.; Stevens, A.; Coeckelberghs, E.; Onkelinx, S.; Thomaes, T.; Delecluse, C.; Budts, W.; Vanhees, L. (International Journal of Cardiology, 2011)
Background: Exercise capacity in grown-ups with congenital heart disease (GUCH) is mostly reported by peak oxygen consumption (peak VO2). Our aim was to evaluate the maximal character of exercise tests, and to investigate submaximal measures of exercise capacity. Methods: Adults with Coarctation of the Aorta (COA, n = 155), Tetralogy of Fallot (TOF, n = 98), dextro-Transposition of the Great Arteries (dTGA, n = 68) and Univentricular Heart (UVH, n = 10), and 122 healthy adults performed cardiopulmonary exercise testing until exhaustion. Gas exchange was measured breath by breath. The maximal performance of the test was evaluated by respiratory exchange ratio (RER), ventilatory equivalent for oxygen and Borg scale. Oxygen uptake efficiency slope (OUES), VE/VCO2 slope and VO2/WR slope were calculated and ventilatory anaerobic threshold (VAT) was defined. Correlations of these measures with peak VO2 were calculated. Results: GUCH showed significantly lower peak VO2 than controls (p < 0.001), declining from 80% in COA, 74% in TOF, 64% in dTGA, to 55% in UVH. Compared to suggested criteria, mean peak RER and median Borg scale indicated a maximal effort in GUCH, however these results were significantly lower than controls (p < 0.05). OUES, VO2/WR slope and VAT were significantly lower in patients compared to controls. OUES (r = 0.853) and VAT (r = 0.840) correlated best with peak VO2; VO2/WR slope (r = 0.551) and VE/VCO2 slope (r = -0.421) correlated to a lesser degree (p < 0.001). Conclusion: The investigated GUCH show reduced exercise tolerance compared to controls, related to the underlying heart defect. Different expressions of exercise tolerance clearly reveal the same differences in exercise capacity across groups of GUCH. © 2010 Elsevier Ireland Ltd.
Keywords: accuracy; adolescent; adult; anaerobic threshold; article; capnometry; carbon dioxide volume; cardiopulmonary exercise test; cardiovascular parameters; congenital heart disease; controlled study; disease association; exercise intensity; exercise tolerance; female; heart function; human; intermethod comparison; lung gas exchange; major clinical study; male; oxygen uptake efficiency slope; priority journal; task performance; ventilatory efficiency slope; ventilatory equivalent for oxygen

Neurocognitive development and behavioral outcome of 2-year-old children with univentricular heart - Puosi, R.; Korkman, M.; Sarajuuri, A.; Jokinen, E.; Mildh, L.; Mattila, I.; Lönnqvist, T. (Journal of the International Neuropsychological Society, 2011)
Recent advances in the treatment of children with severe congenital heart defects, such as hypoplastic left heart syndrome (HLHS) and other forms of univentricular heart (UVH), have significantly improved their survival rates. However, these children are at risk for various neurodevelopmental deficits. The aim of the present study was to assess cognitive development, expressive language, and behavior in 30-month-old children with univentricular heart. The participants were 22 children with HLHS, 14 with UVH, and 41 healthy control subjects. The Bayley Scales of Infant Development II, MacArthur Communicative Development Inventories, and Child Behavior Checklist were used for assessments. The results revealed that children with HLHS exhibited a significantly lower mean mental development index, more delays in expressive language functions, and more behavioral problems than did the control children. Two children with HLHS (9%) had mental development indexes below 50, indicating significantly delayed performance. The children with UVH differed from the control children with respect to their lower mean mental development index. These findings suggest that at the age of 30 months, neurodevelopmental deficits are especially prevalent in children with HLHS. Thus, early developmental screening, intervention, and neuropsychological follow-up until school age is recommended particularly for the children with HLHS. © Copyright The International Neuropsychological Society 2011.
Keywords: article; behavior disorder; chi square distribution; cognitive defect; congenital heart malformation; developmental disorder; female; heart ventricle; human; infant; language disability; male; neurologic examination; neuropsychological test; pathology; pathophysiology; preschool child; severity of illness index

The Impact of Extracorporeal Membrane Oxygenation on Survival in Pediatric Patients With Respiratory and Heart Failure: Review of Our Experience - Goto, T.; Suzuki, Y.; Suzuki, Y.; Osanai, A.; Aoki, K.; Yamazaki, A.; Daitoku, K.; Fukuda, I. (Artificial Organs, 2011)
Extracorporeal membrane oxygenation (ECMO) is widely used for circulatory support in pediatric cardiac patients with low cardiac output and hypoxemia. We retrospectively evaluated the efficacy of ECMO support for respiratory and heart failure in infants and children. From April 2002 to February 2011, 14 patients aged 19 days to 20 years old (average 44 months), with body weight 2.6kg to 71kg (median 14.1kg), underwent ECMO support for failing cardiac function, hypoxemia, and low cardiac output syndrome. In 12 patients, ECMO was introduced after operation for congenital heart disease (four with complete repair including Fontan circulation, and eight with palliative repair). In one patient, ECMO was introduced after partial pulmonary resection for congenital cystic adenomatoid malformation because of respiratory failure. ECMO was introduced in a patient with severe heart failure caused by fulminant myocarditis. Patients' demographics, duration of extracorporeal membrane oxygenation, additional support, and outcomes were analyzed. Ten patients (71%) were successfully weaned from ECMO, and eight patients (57%) were discharged from the hospital. The mean duration of ECMO support was 332h (range 11-2030h). Although management of the ECMO circuit, including anticoagulation (activated clotting time: 150-250), was conducted following the institutional practice guidelines, it was difficult to control the bleeding. Seven patients required renal replacement therapy during ECMO support using peritoneal dialysis or continuous hemodiafiltration. Five patients had additional operative procedures: systemic-pulmonary shunt in two, bidirectional Glenn takedown with right modified Blalock-Taussig shunt, total cavopulmonary connection takedown, and redo ECMO in one patient each. The patient who had the longest ECMO support for respiratory failure due to acute respiratory distress syndrome after lung surgery was successfully weaned from ECMO because high-frequency oscillation (HFO) improved respiratory function. ECMO for heart and respiratory failure in infants and children is effective and allows time for recovery of cardiac dysfunction and acute hypoxic insult. The long-term ECMO support for over 2000h was very rare, but it was possible to wean this patient from ECMO using HFO. © 2011, Copyright the Authors. Artificial Organs © 2011, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: adolescent; adult; anticoagulant therapy; article; Blalock Taussig shunt; cardiopulmonary insufficiency; child; clinical article; congenital heart disease; continuous hemodiafiltration; cystic adenomatoid malformation; extracorporeal oxygenation; Fontan procedure; forward heart failure; Glenn shunt; human; hypoxemia; infant; lung resection; myocarditis; palliative therapy; preschool child; priority journal; renal replacement therapy; retrospective study; school child; survival; systemic pulmonary shunt

Successful use of extracorporeal membrane oxygenation for pH1N1-induced refractory hypoxemia in a child with hypoplastic left heart syndrome - Gandhi, N.N.; Hartman, M.E.; Williford, W.L.; Peters, M.A.; Cheifetz, I.M.; Turner, D.A. (Pediatric Critical Care Medicine, 2011)
Objective: To report the first successful use of extracorporeal membrane oxygenation for acute respiratory distress syndrome secondary to 2009 pH1N1 influenza A infection in a child status post the Fontan operation for hypoplastic left heart syndrome. Design: Individual case report. Setting: Pediatric intensive care unit. PATIENT:: We describe a 7-yr-old boy with a history of the Fontan operation for hypoplastic left heart syndrome admitted with acute respiratory distress syndrome secondary to 2009 pH1N1 influenza A infection. Intervention: Cannulation for venoarterial extracorporeal membrane oxygenation. Measurements and Main Results: In this patient with a history of complex congenital heart disease and repair, extracorporeal membrane oxygenation was a successful rescue therapy for refractory pH1N1-induced respiratory failure. Conclusion: Extracorporeal membrane oxygenation can be successfully applied for refractory respiratory failure, even in the setting of significant underlying comorbidity. With emerging data to support the role of extracorporeal membrane oxygenation in improving mortality for refractory hypoxemia secondary to pH1N1, it is prudent to strongly consider the use of extracorporeal support in patients with underlying diseases or comorbidities that may have previously precluded them from being candidates for this therapy. © 2011 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: epinephrine; antibiotic agent; hydrocortisone; nitric oxide; oseltamivir; vasopressin; adult respiratory distress syndrome; airway pressure; arteriovenous shunt; article; artificial ventilation; case report; child; extracorporeal oxygenation; Fontan procedure; hemodialysis; human; hypoplastic left heart syndrome; hypoxemia; influenza A (H1N1); lung function; lung resistance; male; oxygen saturation; polymerase chain reaction; positive pressure ventilation; priority journal; school child; subdural hematoma

Recurrent delirium after surgery for congenital heart disease in an infant - Madden, K.; Turkel, S.; Jacobson, J.; Epstein, D.; Moromisato, D.Y. (Pediatric Critical Care Medicine, 2011)
Objective: The objective of this article is to describe a case of recurrent delirium after cardiac surgery in an infant. Design: Case report. The institutional review board at Children's Hospital Los Angeles waived the need for informed consent. Setting: Cardiothoracic intensive care unit in a freestanding children's hospital. PATIENT:: A male infant with hypoplastic left heart syndrome who developed delirium on consecutive admissions to the cardiothoracic intensive care unit after cardiac surgery. Intervention: Pharmacologic intervention using the atypical antipsychotic olanzapine. Measurements and Main Results: The symptoms of delirium resolved with the initiation and continuation of olanzapine on both occasions. Conclusion: Delirium is a common, but often unrecognized, diagnosis in the intensive care unit. Its early recognition and treatment may prevent unnecessary use of narcotics and benzodiazepines, decrease length of stay and may improve long-term neurocognitive function. This case report describes an infant who developed discrete, consecutive episodes of delirium following surgery for congenital heart disease. Both episodes were treated effectively with olanzapine. © 2011 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: benzodiazepine derivative; codeine; ibuprofen; lorazepam; morphine; olanzapine; opiate derivative; paracetamol; article; artificial ventilation; bedtime dosage; case report; congestive heart failure; delirium; extracorporeal oxygenation; heart surgery; hospitalization; human; hypoplastic left heart syndrome; infant; insomnia; intensive care unit; male; priority journal; restlessness; treatment response

High-frequency oscillatory ventilation and short-term outcome in neonates and infants undergoing cardiac surgery: A propensity score analysis - Bojan, M.; Gioanni, S.; Mauriat, P.; Pouard, P. (Critical Care, 2011)
Introduction: Experience with high-frequency oscillatory ventilation (HFOV) after congenital cardiac surgery is limited despite evidence about reduction in pulmonary vascular resistance after the Fontan procedure. HFOV is recommended in adults and children with acute respiratory distress syndrome. The aim of the present study was to assess associations between commencement of HFOV on the day of surgery and length of mechanical ventilation, length of Intensive Care Unit (ICU) stay and mortality in neonates and infants with respiratory distress following cardiac surgery.Methods: A logistic regression model was used to develop a propensity score, which accounted for the probability of being switched from conventional mechanical ventilation (CMV) to HFOV on the day of surgery. It included baseline characteristics, type of procedure and postoperative variables, and was used to match each patient with HFOV with a control patient, in whom CMV was used exclusively. Length of mechanical ventilation, ICU stay and mortality rates were compared in the matched set.Results: Overall, 3,549 neonates and infants underwent cardiac surgery from January 2001 through June 2010, 120 patients were switched to HFOV and matched with 120 controls. After adjustment for the delay to sternal closure, duration of renal replacement therapy, occurrence of pulmonary hypertension and year of surgery, the probability of successful weaning over time and the probability of ICU delivery over time were significantly higher in patients with HFOV, adjusted hazard ratios and 95% confidence intervals: 1.63, 1.17 to 2.26 (P = 0.004). and 1.65, 95% confidence intervals: 1.20 to 2.28 (P = 0.002) respectively. No association was found with mortality.Conclusions: When commenced on the day of surgery in neonates and infants with respiratory distress following cardiac surgery, HFOV was associated with shorter lengths of mechanical ventilation and ICU stay than CMV. © 2011 Bojan et al.; licensee BioMed Central Ltd.
Keywords: epinephrine; milrinone; acute kidney failure; article; artificial ventilation; cohort analysis; extracorporeal oxygenation; heart surgery; high frequency oscillatory ventilation; human; infant; intensive care; intensive care unit; length of stay; major clinical study; newborn; outcome assessment; pediatric surgery; priority journal; pulmonary hypertension; renal replacement therapy; respiratory distress; retrospective study

Progress of surgical treatment of pediatric congenital heart disease - Xu, Z.-W. (Journal of Shanghai Jiaotong University (Medical Science), 2011)
In recent years, the surgical treatment and operative procedure for congenital heart disease (CHD) have been greatly improved. The surgical results of hypoplastic left heart syndrome (HLHS) have been improved by modified operative procedure and intervention. With proper management of the right ventricle outflow tract in tetralogy of Fallot (TOF), right ventricle heart function can be improved after operation. The surgical repair of pulmonary venous obstruction after operation of total abnormal pulmonary venous connection (TAPVC), and the renewed operative procedure of transposition of the great arteries (TGA) and congenital corrected transposition of the great arteries (ccTGA) facilitate the rational surgical treatment of complex CHD. With improvement of operative procedure for CHD, the operative successful rate is increased, the incidence of complications is decreased, and the quality of life and long-term surgical outcomes are improved.
Keywords: article; congenital heart disease; Fallot tetralogy; great vessels transposition; heart function; heart right ventricle outflow tract; heart surgery; human; hypoplastic left heart syndrome; lung vein drainage anomaly; pulmonary vein obstruction; pediatric surgery; quality of life; treatment outcome

Fetal and post-natal diagnosis of major congenital heart disease: Implications for medical and psychological care in the current era - Sholler, G.F.; Kasparian, N.A.; Pye, V.E.; Cole, A.D.; Winlaw, D.S. (Journal of Paediatrics and Child Health, 2011)
Aim: The fetal or post-natal diagnosis of major congenital cardiac abnormality has important medical and psychological consequences. Methods: We reviewed infants who underwent cardiac surgery in the first year of life at the Heart Centre for Children, The Children's Hospital at Westmead during 2009. The aims of this study were to: (i) examine the key features of cardiac diagnosis and clinical outcome, and (ii) consider how these data can inform priorities for the delivery of clinical services. Results: Over the 12-month study period, a first cardiac surgical procedure was performed on 195 infants, with 85 infants (44%) diagnosed in the antenatal period. Of the total sample, a subset of 90 babies (46%) underwent their first procedure in the neonatal period, with 62% having had a fetal diagnosis. Major intracardiac lesions including truncus arteriosus (100%), single ventricular lesions (83%), pulmonary atresia with ventricular septal defect (78%) and transposition of the great arteries (53%) were diagnosed prior to birth. Improved haemodynamic stability at initial presentation was found in those with a fetal diagnosis. The overall mortality rate for all patients was 6.1% at 12 months, with a higher mortality in infants with single ventricle. Conclusions: The contemporary paradigm of care for infants with major congenital heart disease requires a multidisciplinary approach to care, with improvements in clinician-clinician and clinician-family communication, and psychological support and education for families. Changes in the allocation of resources are required to meet this model of best practice. © 2011 The Authors.
Keywords: arterial trunk; article; clinical feature; congenital heart disease; female; health care delivery; heart surgery; heart ventricle septum defect; hemodynamic monitoring; human; infant; major clinical study; male; medical care; mental health; mortality; postnatal care; prenatal diagnosis; prenatal period; priority journal; pulmonary valve atresia

Pediatric sub-specialist controversies in the treatment of congenital heart disease in trisomy 13 or 18. - Yates, A.R.; Hoffman, T.M.; Shepherd, E.; Boettner, B.; McBride, K.L. (Journal of genetic counseling, 2011)
Trisomy 13 and 18 are associated with congenital heart disease. Cardiac palliation has been reported in the literature, but is not usually done in this population. Thus, a multi-disciplinary team may experience controversy in formulating a care plan that includes cardiac intervention. Our objective was to determine differences in recommendations for cardiac intervention in this population between physicians specializing in pediatric cardiac critical care, neonatology, and genetics. A web-based survey was performed between April 2007 and August 2008. This survey evaluated surgical and transcatheter cardiac palliations that had been performed for individuals with trisomy 13 or 18 at the respondent's institution, the respondent's recommendations for cardiac intervention in hypothetical symptomatic patients with trisomy 13 or trisomy 18 and the influence of parental preference on these recommendations. Eight hundred fifty-nine responses were obtained from a primarily academic practice setting (59%). Cardiologists were most likely to recommend intervention; low risk interventions were recommended by 32% of cardiologists, 7% of neonatologists and 20% of geneticists. Parental request to intervene resulted in a 3 fold increased in the likelihood of all specialist recommending intervention. Counseling of families frequently occurred by multiple sub specialists (50%) and there was frequently (71%) a difference in opinion. Individuals with trisomy 13 or 18 are receiving cardiac intervention at many institutions. Cardiologists were more likely than geneticists or neonatologists to recommend intervention on all heart lesions other than single ventricle palliation which no specialists recommended. Parental wishes that "everything be done" significantly influenced all specialists' recommendations.
Keywords: article; chromosome 13; chromosome 18; cohort analysis; congenital heart malformation; female; genetics; human; male; workforce; pediatrics; physician; psychological aspect; trisomy

Undiagnosed heart disease leading to sudden unexpected death in childhood: A retrospective study - Ilina, M.V.; Kepron, C.A.; Taylor, G.P.; Perrin, D.G.; Kantor, P.F.; Somers, G.R. (Pediatrics, 2011)
OBJECTIVES: Heart disease accounts for a significant proportion of sudden unexpected deaths among children. We describe here demographic features, pathological conditions, and the frequency of premonitory symptoms in a retrospective series of cases of sudden unexpected cardiac death (SUCD) attributable to undiagnosed structural heart disease. METHODS: A chart review of autopsies involving children 0 to 17 years of age that were performed at the Hospital for Sick Children (Toronto, Ontario, Canada) between 1984 and 2003 was conducted. Cases of sudden unexpected death within 24 hours after clinical presentation with previously undetected fatal heart disease were included. Cases with multiple or thoracic trauma and chronic or multisystem disease were excluded. RESULTS: During the 20-year study period, 4926 autopsies were performed. A total of 103 cases (2.1%), involving 51 male patients and 52 female patients 1 day to 15 years of age (mean: 2.9 ± 4.2 years), were diagnosed as having SUCD. The most common diagnoses were myocarditis (n-37 [35.9%]), hypoplastic left heart syndrome (HLHS) (n = 19 [18.4%]), dilated cardiomyopathy (DCM) (n = 16 [16.5%]), coronary artery anomalies (n = 6 [5.8%]), and aortic stenosis (n = 5 [4.9%]). There was a significant difference in the mean age of presentation between leading causes of SUCD (6.5 days for HLHS, 1.7 years for DCM, and 5.4 years for myocarditis; P < .0001). Of 103 cases, 27 (26.2%) had premonitory symptoms documented. CONCLUSION: SUCD accounted for 2.1% of all autopsies, and HLHS, DCM, and myocarditis were the 3 most common diagnoses, which presented at increasing ages. Copyright © 2011 by the American Academy of Pediatrics.
Keywords: adolescent; age distribution; aortic stenosis; article; autopsy; Canada; child; childhood; congestive cardiomyopathy; coronary artery anomaly; demography; female; heart disease; human; hypoplastic left heart syndrome; infant; major clinical study; male; medical record review; myocarditis; newborn; preschool child; priority journal; retrospective study; school child; sudden death; symptom

Perioperative cerebral and somatic oxygenation in neonates with hypoplastic left heart syndrome or transposition of the great arteries - Uebing, A.; Furck, A.K.; Hansen, J.H.; Nufer, E.; Scheewe, J.; Dütschke, P.; Jung, O.; Kramer, H.-H. (Journal of Thoracic and Cardiovascular Surgery, 2011)
Objective: Significant depression in cerebral oxygen saturation has been observed in patients with hypoplastic left heart syndrome (HLHS) undergoing Norwood operations. We monitored cerebral oxygen saturation with near-infrared spectroscopy before and after this procedure. Patients with transposition of great arteries (TGA) before and after arterial switch operation were also studied to elucidate whether post-cardiopulmonary bypass (CPB) changes in cerebral oxygen saturation are related to CPB or hemodynamic alterations inherent in single-ventricle physiology. Methods: We monitored 33 patients with HLHS and 20 with TGA 24 hours before and 48 hours after CPB. In addition to cerebral oxygen saturation, routine measurements of oxygen transport and delivery were performed. Results: Preoperatively, cerebral oxygen saturation was higher in patients with HLHS than with TGA (61% ± 7% vs 56% ± 8%, P = .04). After CPB, cerebral oxygen saturation was markedly depressed in both groups but increased toward end of monitoring (HLHS vs TGA minimal value 42% ± 12% vs 54% ± 11%, P < .001, value 48 hours after CPB 62% ± 7% vs 80% ± 8%, P < .0001). Routine measures of oxygen delivery, such as arterial and central venous oxygen saturations, were similar at minimal cerebral oxygen saturation and 48 hours after CPB. Conclusions: Depression of cerebral oxygen saturation is prevalent among neonates with congenital heart disease regardless of whether univentricular or biventricular circulation is present, suggesting that cerebral desaturation is mainly induced by CPB's effect on cerebral blood flow. Routine measures of oxygen delivery fail to indicate cerebral desaturation. Copyright © 2011 by The American Association for Thoracic Surgery.
Keywords: furosemide; nitroprusside sodium; phentolamine mesylate; prostaglandin E1; adverse outcome; arterial switch operation; article; brain oxygen tension; cardiovascular surgery; child; clinical article; female; great vessels transposition; hemodynamics; human; hypoplastic left heart syndrome; low drug dose; male; near infrared spectroscopy; Norwood procedure; oxygen saturation; preoperative evaluation; priority journal; school child; tissue oxygenation

A maternal dietary pattern characterised by fish and seafood in association with the risk of congenital heart defects in the offspring - Obermann-Borst, S.A.; Vujkovic, M.; De Vries, J.H.; Wildhagen, M.F.; Looman, C.W.; De Jonge, R.; Steegers, E.A.P.; Steegers-Theunissen, R.P.M. (BJOG: An International Journal of Obstetrics and Gynaecology, 2011)
Objective To identify maternal dietary patterns related to biomarkers of methylation and to investigate associations between these dietary patterns and the risk of congenital heart defects (CHDs) in the offspring. Design Case-control study. Setting Western part of the Netherlands, 2003-08. Population One hundred and seventy-nine mothers of children with CHD and 231 mothers of children without a congenital malformation. Methods Food intake was obtained by food frequency questionnaires. The reduced rank regression method was used to identify dietary patterns related to the biomarker concentrations of methylation in blood. Main outcome measures Dietary patterns, vitamin B and homocysteine concentrations, biomarkers of methylation (S-adenosylmethionine [SAM] and S-adenosylhomocysteine [SAH]) and the risk of CHD estimated by odds ratios and 95% confidence intervals. Results The one-carbon-poor dietary pattern, comprising a high intake of snacks, sugar-rich products and beverages, was associated with SAH (β = 0.92, P < 0.001). The one-carbon-rich dietary pattern with high fish and seafood intake was associated with SAM (β = 0.44, P < 0.001) and inversely with SAH (β = -0.08, P < 0.001). Strong adherence to this dietary pattern resulted in higher serum (P < 0.05) and red blood cell (P < 0.01) folate and a reduced risk of CHD in offspring: odds ratio, 0.3 (95% confidence interval, 0.2-0.6). Conclusions The one-carbon-rich dietary pattern, characterised by the high intake of fish and seafood, is associated with a reduced risk of CHD. This finding warrants further investigation in a randomised intervention trial. © 2011 The Authors BJOG An International Journal of Obstetrics and Gynaecology © 2011 RCOG.
Keywords: biological marker; folic acid; homocysteine; s adenosylhomocysteine; ademetionine; sugar; vitamin B group; adult; alcohol consumption; aortic coarctation; aortic valve stenosis; article; beverage; caloric intake; cardiovascular risk; congenital heart malformation; controlled study; disease association; educational status; erythrocyte; Fallot tetralogy; fast food; female; fish; food frequency questionnaire; food intake; great vessels transposition; heart ventricle septum defect; human; human experiment; hypoplastic left heart syndrome; maternal dietary pattern; methylation; Netherlands; normal human; priority journal; progeny; pulmonary valve stenosis; risk assessment; sea food; smoking

Maternal injuries during the periconceptional period and the risk of birth defects, National Birth Defects Prevention Study, 1997-2005 - Tinker, S.C.; Reefhuis, J.; Dellinger, A.M.; Jamieson, D.J. (Paediatric and Perinatal Epidemiology, 2011)
Tinker SC, Reefhuis J, Dellinger AM, Jamieson DJ, the National Birth Defects Prevention Study. Maternal injuries during the periconceptional period and the risk of birth defects, National Birth Defects Prevention Study, 1997-2005. Paediatric and Perinatal Epidemiology 2011; 25: 487-496. Maternal injuries during pregnancy are common (â̂7% prevalence). However, few studies have examined the association between maternal injuries and birth defects. The National Birth Defects Prevention Study is a population-based case-control study of birth defects in 10 US states. Cases were ascertained through surveillance; controls were randomly selected from infants delivered without major birth defects in the study regions. Mothers completed a telephone interview on exposures before and during pregnancy, including injuries. We assessed associations between periconceptional (month before until the end of the third month of pregnancy) maternal injuries and birth defects. We used logistic regression to estimate adjusted odds ratios (AORs) and 95% confidence intervals (CI). Periconceptional injuries were associated with interrupted aortic arch type B [AOR = 5.2, 95% CI 1.2, 23.2]; atrioventricular septal defect [AOR = 2.2, 95% CI 1.1, 4.4]; pulmonary atresia [AOR = 3.2, 95% CI 1.6, 6.4]; tricuspid atresia [AOR = 2.8, 95% CI 1.2, 6.7]; hypoplastic left heart syndrome [AOR = 2.0, 95% CI 1.1, 3.4]; anorectal atresia/stenosis [AOR = 1.7, 95% CI 1.0, 2.7]; longitudinal limb deficiency [AOR = 2.1, 95% CI 1.1, 3.9]; and gastroschisis [AOR = 1.8, 95% CI 1.2, 2.8]. Associations with longitudinal limb deficiency, gastroschisis and hypoplastic left heart syndrome were stronger for intentional injuries. Our results suggest maternal injury during the periconceptional period, particularly those inflicted intentionally, may be associated with select birth defects. This analysis was hypothesis-generating, with many associations tested. Further research is warranted. © 2011 Blackwell Publishing Ltd.
Keywords: adult; amnion band syndrome; anencephalus; anophthalmia; anterior eye chamber disease; anus atresia; aortic arch interruption; aortic coarctation; aortic stenosis; article; automutilation; bile duct atresia; cholestasis; congenital malformation; bladder exstrophy; cleft lip palate; congenital cataract; controlled study; craniofacial synostosis; diaphragm hernia; disease association; encephalocele; esophagus atresia; esophagus stenosis; Fallot tetralogy; female; gastroschisis; glaucoma; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart ventricle septum defect; holoprosencephaly; human; hydrocephalus; hypoplastic left heart syndrome; hypospadias; interview; intestine atresia; intestine stenosis; kidney agenesis; limb defect; lung vein drainage anomaly; major clinical study; maternal disease; microphthalmia; microtia; omphalocele; pregnancy; pulmonary valve atresia; pulmonary valve stenosis; spinal dysraphism; statistical analysis; telephone; tricuspid valve atresia

A multicenter, randomized trial comparing heparin/warfarin and acetylsalicylic acid as primary thromboprophylaxis for 2 years after the Fontan procedure in children - Monagle, P.; Cochrane, A.; Roberts, R.; Manlhiot, C.; Weintraub, R.; Szechtman, B.; Hughes, M.; Andrew, M.; McCrindle, B.W. (Journal of the American College of Cardiology, 2011)
Objectives: The purpose of this study was to compare the safety and efficacy of acetylsalicylic acid (ASA) and warfarin for thromboprophylaxis after the Fontan procedure. Background: Fontan surgery is the definitive palliation for children with single-ventricle physiology. Thrombosis is an important complication; the optimal thromboprophylaxis strategy has not been determined. Methods: We performed a multicenter international randomized trial of primary prophylactic anticoagulation after Fontan surgery. Patients were randomized to receive for 2 years either ASA (5 mg/kg/day, no heparin phase) or warfarin (started within 24 h of heparin lead-in; target international normalized ratio: 2.0 to 3.0). Primary endpoint (intention to treat) was thrombosis, intracardiac or embolic (all events adjudicated). At 3 months and 2 years after the Fontan procedure, transthoracic and transesophageal echocardiograms were obtained as routine surveillance. Major bleeding and death were primary adverse outcomes. Results: A total of 111 eligible patients were randomized (57 to ASA, 54 to heparin/warfarin). Baseline characteristics for each group were similar. There were 2 deaths unrelated to thrombosis or bleeding. There were 13 thromboses in the heparin/warfarin group (3 clinical, 10 routine echo) and 12 thromboses in the ASA group (4 clinical, 8 routine echo). Overall freedom from thrombosis 2 years after Fontan surgery was 19%, despite thrombosis prophylaxis. Cumulative risk of thrombosis was persistent but varying and similar for both groups (p = 0.45). Major bleeding occurred in 1 patient in each group. Conclusions: There was no significant difference between ASA and heparin/warfarin as primary thromboprophylaxis in the first 2 years after Fontan surgery. The thrombosis rate was suboptimal for both regimens, suggesting alternative approaches should be considered. (International Multi Centre Randomized Clinical Trial Of Anticoagulation In Children Following Fontan Procedures; NCT00182104) © 2011 American College of Cardiology Foundation.
Keywords: NCT00182104; acetylsalicylic acid; heparin; warfarin; article; bleeding; child; controlled study; female; Fontan procedure; gastrointestinal hemorrhage; human; loading drug dose; major clinical study; male; mortality; multicenter study; patient compliance; preschool child; priority journal; randomized controlled trial; risk assessment; thrombosis; transesophageal echocardiography; treatment outcome

Significance of the residual aortic obstruction in multistage repair of hypoplastic left heart syndrome - Januszewska, K.; Kozlik-Feldmann, R.; Kordon, Z.; Urschel, S.; Netz, H.; Reichart, B.; Malec, E. (European Journal of Cardio-thoracic Surgery, 2011)
Objective: The population of children who received right ventricle-to-pulmonary artery shunt (RV-PA) at Norwood procedure (NP) is growing, but limited data are available regarding the long-term outcome. The aim of this study was to present operative outcomes and mid-term hemodynamics and to assess the impact of the residual aortic obstruction on the results in patients undergoing three-staged surgery with RV-PA application at NP. Methods: Between June 2001 and June 2009, 229 children with hypoplastic left heart syndrome (HLHS) and variants underwent NP with RV-PA; 172 have proceeded to stage II and 95 to stage III. The medical records (clinical data, echocardiographic records, cardiac catheterization reports, electrocardiograms, and surgical notes) were retrospectively reviewed. Results: The later era of NP was associated with significantly better outcome (2001-2004: 1- and 5-years' survival were 64.3% and 59.8%, respectively; 2005-2009: 1- and 4-years' survival were 93.1% and 86.9%, respectively) (p< 0.001). There was no association between long-term survival and diagnosis (HLHS/HLHS variant) (p= 0.39). The incidence of depressed ventricular function and moderate or severe systemic atrioventricular valve regurgitation among the children who required balloon aortoplasty (BA) before stage II surgery was significantly higher than in children without aortic arch obstruction (p= 0.027, p= 0.008, respectively). In midterm follow-up, BA had no significant influence on the actuarial survival (p= 0.089). No ventricular arrhythmias were noticed at any stage. Conclusions: The RV-PA shunt is a safe technique that does not seem to impair systolic or electrical ventricular function; its outcomes continue to improve with growing experience. Combined cardiologic interventional and surgical procedures are required to optimize the outcomes. © 2010 European Association for Cardio-Thoracic Surgery.
Keywords: aortic occlusion; aortoplasty; article; child; disease severity; female; follow up; heart ventricle function; hemodynamics; human; hypoplastic left heart syndrome; infant; major clinical study; male; medical record review; mitral valve regurgitation; Norwood procedure; preschool child; priority journal; right ventricle to pulmonary artery conduit; school child; survival; treatment outcome

The fontan operation: The pursuit of associated lesions and cumulative trauma - Hannan, R.L.; Zabinsky, J.A.; Salvaggio, J.L.; Rossi, A.F.; Khan, D.M.; Alonso, F.A.; Ojito, J.W.; Nykanen, D.G.; Zahn, E.M.; Burke, R.P. (Pediatric Cardiology, 2011)
Our programmatic approach to the Fontan operation has evolved to include using an extracardiac conduit with aggressive presumptive treatment of associated lesions either in the catheterization laboratory or the operating room. Fenestration is used selectively based on hemodynamics, anatomy, and presence of associated lesions. We reviewed our experience to determine the effectiveness and outcome of this strategy and to assess the cumulative trauma to the patients. The records of 137 consecutive patients who underwent Fontan at Miami Children's Hospital from 1995 to 2008 were reviewed. At mean follow up of 5.76 years, freedom from death or transplantation is 94.2% (129/137). Median age at operation was 4.6 years. Longer length of stay correlated with older operative age (P = 0.0056). Pacemakers were implanted in 11.7% (16/137). Additional (not pre-Glenn or pre-Fontan) interventional catheterizations were performed in 51.8% (71/137). Additional operations were done in 10.2% (14/137). No patient has required replacement or revision of the extracardiac conduit. Our current approach to the Fontan operation provides acceptable midterm results. The pursuit of residual lesions results in a significant number of additional interventional catheterizations and operative procedures but might have an important influence on long-term survival after the Fontan procedure. © 2011 The Author(s).
Keywords: angioplasty; aortic stenosis; article; artificial heart pacemaker; atrioventricular canal; child; Ebstein anomaly; Fallot tetralogy; follow up; Fontan procedure; great vessels transposition; heart catheterization; heart right ventricle double outlet; heart ventricle septum defect; hospitalization; human; hypoplastic left heart syndrome; length of stay; major clinical study; medical record review; mitral valve atresia; preschool child; pulmonary valve atresia; retrospective study; school child; stent; survival; thoracotomy; thorax drainage; treatment outcome; tricuspid valve atresia; tricuspid valve disease

Infants with complex congenital heart disease in the Emergency Department - Daniels, S.R. (Journal of Pediatrics, 2011)
Keywords: article; cardiologist; child hospitalization; complex congenital heart disease; congenital heart disease; consultation; cooperation; emergency ward; health care facility; health care utilization; heart single ventricle; human; infant; infant disease; intensivist; medical education; outcome assessment; patient care; pediatrician; primary medical care; priority journal; simulation

Maternal alcohol drinking pattern during pregnancy and the risk for an offspring with an isolated congenital heart defect and in particular a ventricular septal defect or an atrial septal defect - Strandberg-Larsen, K.; Skov-Ettrup, L.S.; Grønbæk, M.; Andersen, A.-M.N.; Olsen, J.; Tolstrup, J. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2011)
This cohort study examines the possible association between maternal alcohol intake, including binge drinking, during pregnancy, and the subsequent risk of having a child with an isolated congenital heart defect and, more specifically, with the isolated form of ventricular septal defect (VSD) or of an atrial septal defect (ASD). Methods: Participants were 80,346 pregnant women who were enrolled into the Danish National Birth Cohort in 1996-2002 and gave birth to a live-born singleton without any chromosome anomalies. Twice during pregnancy these women were asked about their intake of alcohol. Few (if any) women with an excessive/abusive intake of alcohol were enrolled into the Danish National Birth Cohort. Results: Through linkage with the National Hospital Discharge Registry, we identified 477 infants with a diagnosis of isolated congenital heart defect registered at any time during their first 31/2-years of life; they included 198 infants with a VSD and 145 with an ASD. Neither the number of episodes of binge drinking nor binge drinking during three different developmental periods was associated with VSD or ASD. Women drinking 1/2-11/2, 2, and 3+ drinks of alcohol per week had adjusted prevalence ratios of delivering an infant with a VSD of 1.22 (95% CI = 0.90-1.66); 1.38 (95% CI = 0.83-2.28); and 1.10 (95% CI = 0.54-2.23), respectively. The test for trend was 0.29. Conclusions: Prenatal exposure to low-to-moderate levels of alcohol on a weekly basis or occasional binge drinking during the early part of pregnancy was not statistical significantly associated with the prevalence of isolated VSD and ASD in offspring. © 2011 Wiley-Liss, Inc.
Keywords: adult; alcohol abuse; alcohol consumption; aortic coarctation; aorta valve atresia; aortic valve disease; aortic valve stenosis; arterial trunk; article; atrioventricular septal defect; child; chromosome aberration; cohort analysis; congenital heart malformation; drinking behavior; Ebstein anomaly; Fallot tetralogy; female; fetus risk; great vessels transposition; heart atrium septum defect; heart single ventricle; heart ventricle septum defect; hospital discharge; human; hypoplastic left heart syndrome; hypoplastic right heart; lung vein drainage anomaly; major clinical study; maternal behavior; pregnant woman; prenatal exposure; preschool child; priority journal; tricuspid valve atresia; tricuspid valve stenosis

Evaluation of image quality and radiation dose at prospective ECG-triggered axial 256-slice multi-detector CT in infants with congenital heart disease - Huang, M.-P.; Liang, C.-H.; Zhao, Z.-J.; Liu, H.; Li, J.-L.; Zhang, J.-E.; Cui, Y.-H.; Yang, L.; Liu, Q.-S.; Ivanc, T.B.; Vembar, M. (Pediatric Radiology, 2011)
Background: There are a limited number of reports on the technical and clinical feasibility of prospective electrocardiogram (ECG)-gated multi-detector computed tomography (MDCT) in infants with congenital heart disease (CHD). Objective: To evaluate image quality and radiation dose at weight-based low-dose prospectively gated 256-slice MDCT angiography in infants with CHD. Materials and methods: From November 2009 to February 2010, 64 consecutive infants with CHD referred for pre-operative or post-operative CT were included. All were scanned on a 256-slice MDCT system utilizing a low-dose protocol (80 kVp and 60-120 mAs depending on weight: 60 mAs for ≤3 kg, 80 mAs for 3.1-6 kg, 100 mAs for 6.1-10 kg, 120 mAs for 10.1-15 kg). Results: No serious adverse events were recorded. A total of 174 cardiac deformities, confirmed by surgery or heart catheterization, were studied. The sensitivity of MDCT for cardiac deformities was 97.1%; specificity, 99.4%; accuracy, 95.9%. The mean heart rate during scan was 136.7 ± 14.9/min (range, 91-160) with a corresponding heart rate variability of 2.8 ± 2.2/min (range, 0-8). Mean scan length was 115.3 ± 11.7 mm (range, 93.6-143.3). Mean volume CT dose index, mean dose-length product and effective dose were 2.1 ± 0.4 mGy (range, 1.5-2.8), 24.7 ± 5.9 mGy•cm (range, 14.7-35.8) and 1.6 ± 0.3 mSv (range, 1.1-2.5), respectively. Diagnostic-quality images were achieved in all cases. Satisfactory diagnostic quality for visualization of all/proximal/distal coronary artery segments was achieved in 88.4/98.8/80.0% of the scans. Conclusion: Low-dose prospectively gated axial 256-slice CT angiography is a valuable tool in the routine clinical evaluation of infants with CHD, providing a comprehensive three-dimensional evaluation of the cardiac anatomy, including the coronary arteries. © 2011 Springer-Verlag.
Keywords: iopromide; accuracy; aortic arch interruption; aortic coarctation; aortopulmonary septal defect; article; computed tomographic angiography; congenital heart disease; coronary artery; electrocardiogram; Fallot tetralogy; female; great vessels transposition; heart atrium septum defect; heart catheterization; heart rate; heart rate variability; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; human; image quality; infant; lung vein drainage anomaly; major clinical study; male; multidetector computed tomography; newborn; patent ductus arteriosus; priority journal; pulmonary valve atresia; radiation dose; sensitivity and specificity; vascular ring; Williams Beuren syndrome; ultravist 300

Parenting children with hypoplastic left heart syndrome: Finding a balance - Lee, A.; Rempel, G.R. (Journal for Specialists in Pediatric Nursing, 2011)
Purpose. This study described the role normalization played for parents related to their young children with hypoplastic left heart syndrome. Design and Methods. The data source for this secondary analysis was 30 interviews with 16 parents. Results. Three themes were identified: normalization, parental perception of child vulnerability, and optimistic appraisal. Parents engaged in a balancing act between worrying about their children's vulnerability and marveling at their children's survival, using normalization as a coping strategy. Practice Implications. Nurses can collaborate with parents to determine strategies to restore a sense of normalcy to simultaneously promote child independence and parent well-being. © 2011, Wiley Periodicals, Inc.
Keywords: adaptive behavior; adult; age; article; Canada; caregiver; child parent relation; cohort analysis; female; follow up; handicapped child; heart surgery; human; hypoplastic left heart syndrome; infant; long term care; male; methodology; middle aged; patient care; preschool child; psychological aspect; risk factor; treatment outcome; vulnerable population

Associations between maternal fever and influenza and congenital heart defects - Oster, M.E.; Riehle-Colarusso, T.; Alverson, C.J.; Correa, A. (Journal of Pediatrics, 2011)
Objective: To examine associations between maternal reports of prenatal fever or influenza and congenital heart defects (CHDs), and to evaluate whether those associations varied with antipyretic use. Study design: We analyzed case infants with CHD (n = 2361) and control infants without CHD (n = 3435) from the Baltimore-Washington Infant Study (1981-1989). Participating mothers were asked whether they experienced a "fever of 101°F or higher," had "influenza (flu)," or used an antipyretic agent (ie, acetaminophen, salicylate, or nonsteroidal anti-inflammatory drug) during the period extending from 3 months before pregnancy through the end of the third month of pregnancy. We used logistic regression to compute ORs and 95% CIs while controlling for potential confounders. Results: There were significant associations between fever and influenza and specific CHDs, namely right-sided obstructive defects (fever: OR, 2.04; 95% CI, 1.27 to 3.27; influenza: OR, 1.75; 95% CI, 1.16 to 2.62) and atrioventricular septal defects in infants with Down syndrome (fever: OR, 1.92; 95% CI, 1.10 to 3.38; influenza: OR, 1.66; 95% CI, 1.04 to 2.63). Maternal antipyretic use in the setting of fever or influenza tended to decrease these associations. Conclusions: Prenatal maternal fever or influenza may be associated with right-sided obstructive lesions in all infants and with atrioventricular septal defects in infants with Down syndrome. The use of antipyretics might attenuate such associations. Copyright © 2011 Mosby Inc. All rights reserved.
Keywords: antipyretic agent; nonsteroid antiinflammatory agent; paracetamol; salicylic acid; aortic coarctation; aortic stenosis; article; congenital heart malformation; controlled study; disease association; Down syndrome; Ebstein anomaly; Fallot tetralogy; female; fever; great vessels transposition; heart atrium septum defect; heart outflow tract obstruction; heart ventricle septum defect; human; hypoplastic left heart syndrome; infant; influenza; major clinical study; male; maternal disease; prenatal disorder; prenatal drug exposure; priority journal; pulmonary valve stenosis; risk assessment; third trimester pregnancy; tricuspid valve atresia; upper respiratory tract infection; urinary tract infection

Challenges on the management of congenital heart disease in developing countries - Mocumbi, A.O.; Lameira, E.; Yaksh, A.; Paul, L.; Ferreira, M.B.; Sidi, D. (International Journal of Cardiology, 2011)
Introduction: While in developed countries prenatal diagnosis is currently used to detect Congenital Heart Disease before (CHD) before birth, in developing countries only a minority of children with CHD is detected and few benefit from surgical treatment. Having created a referral unit for diagnosis and treatment of cardiovascular diseases in a resource-deprived country we designed a study aiming at describing the spectrum and characteristics of CHD and discuss the challenges of its management. Population and methods: We studied retrospectively all patients assisted at a referral unit between 2001 and 2007, collecting epidemiological, clinical, echocardiographic and surgical data from hospital files. Results: We studied 534 patients with median age at diagnosis of 4 years (range 0-79); 296 were females (55.4%). Only 282 (52.8%) patients were diagnosed under the age of two years, and complications were present in 155 (29.0%) at time of diagnosis. We operated 196 patients with mean age of 8 ± 10 years. Only 29 of the 111 complex defects were considered for surgery. The 30-days post-operative mortality was 8/196 (4.0%). The most important post-surgical complications were post pericardectomy syndrome (22). Discussion: A pattern of late presentation accompanied by high rate of complications was found. In resource-deprived settings the approach to the management of CHD emphasizes the treatment of "curable" malformations. Surgery for CHD in these settings must be linked to early detection and a referral system in which general practitioners, pediatricians, obstetricians and cardiologists interact in the design and implementation protocols for diagnosis, management and follow-up of patients. © 2009 Elsevier Ireland Ltd.
Keywords: adolescent; adult; age; aged; aortic aneurysm; aortic valve disease; arterial trunk; article; atrioventricular septal defect; bacterial endocarditis; bleeding; cardiomyopathy; child; congenital heart disease; cyanotic heart disease; developing country; disease severity; Fallot tetralogy; female; great vessels transposition; heart arrhythmia; heart atrium septum defect; heart failure; heart left right shunt; heart right ventricle double outlet; heart right ventricle outflow tract obstruction; heart single ventricle; heart surgery; heart ventricle septum defect; human; Human immunodeficiency virus infection; kidney failure; lung insufficiency; major clinical study; male; malnutrition; mitral valve regurgitation; neurologic disease; neurological complication; palliative therapy; patent ductus arteriosus; polycythemia; postoperative complication; priority journal; pulmonary hypertension; pulmonary valve atresia; pulmonary valve stenosis; reoperation; retrospective study; situs inversus; cerebrovascular accident; surgical mortality; treatment contraindication; treatment refusal; tricuspid valve atresia

The quality of life of young children and infants with chronic medical problems: Review of the literature - Payot, A.; Barrington, K.J. (Current Problems in Pediatric and Adolescent Health Care, 2011)
The question "what makes a good quality of life?" is a philosophical one which could be thought immune to scientific investigations. However, over the last few decades there has been great progress in developing tools to quantify quality of life (QoL) to make comparisons between different health states, evaluate the effectiveness of medical interventions, and describe the life trajectories of individuals or groups. Using a series of vignettes, we explore and review the biomedical literature to demonstrate how QoL is affected by chronic health conditions in childhood, and how it evolves as individuals pass into adulthood. Individuals experiencing serious chronic illnesses generally have reduced health-related QoL: their health status has significant repercussions of their everyday life, but scores are usually much better than healthy individuals expect, and better than physicians predict. Global QoL is more than a health status concept. QoL is a complex relationship between objectivity and subjectivity; it requires substantial and valid facts, and it defines itself by an interpretation of health within different schemes of values: societal, medical, and those of the subject themselves. QoL is dynamic; purely physical influences diminish as individuals age, and psychosocial factors become much more important. Resilience frequently allows adaptation to adverse health states, leading to acceptable QoL for most children with disabilities. © 2011 Mosby, Inc. All rights reserved.
Keywords: dopamine; anxiety; Arnold Chiari malformation; article; attention deficit disorder; auditory screening; brain ventricle dilatation; central venous catheter; cerebral palsy; cesarean section; chest infection; child health care; childhood disease; chronic disease; clubfoot; cognitive defect; colostomy; constipation; coping behavior; depression; extremely low birth weight; family counseling; functional status; handicapped child; health care cost; hearing aid; human; hypoplastic left heart syndrome; infant disease; infection risk; intelligence quotient; intestine perforation; job finding; life expectancy; lung dysplasia; meningomyelocele; motivation; motor development; musculoskeletal stiffness; necrotizing enterocolitis; neonatology; patent ductus arteriosus; physiotherapy; posttraumatic stress disorder; prematurity; quality of life; questionnaire; respiratory arrest; resuscitation; school admission; scoring system; self esteem; sepsis; tissue perfusion; trisomy 13; trisomy 18; unilateral hearing loss; urinary tract infection; very low birth weight; visual analog scale; visual impairment

Experience with bidirectional cavopulmonary anastomosis and modified Fontan operation in patients with single ventricle and concomitant visceral heterotaxy - Yurlov, I.A.; Podzolkov, V.P.; Zelenikin, M.M.; Kovalev, D.V.; Babaev, G.K.; Putiato, N.A.; Zaets, S.B. (Interactive Cardiovascular and Thoracic Surgery, 2011)
The object of our study was to analyze the results of bidirectional cavopulmonary anastomosis (BCPA) and modified Fontan operations (MFO) in patients with a functionally single ventricle and heterotaxy syndrome and to reveal risk factors for these surgical interventions. During 1983-2010, 681 patients underwent BCPA or MFO. Thirty-nine had heterotaxy syndrome. The median follow-up period after BCPA and MFO was nine and 1.5 years, respectively. Risk factors for lethal outcomes were determined by logistic regression analysis. Hospital mortality after BCPA and MFO was 7.9% and 12.5%, respectively and did not significantly differ from patients without heterotaxy. The most frequent hospital complications were heart failure, pleural effusions, and arrhythmias. Late mortality after BCPA and MFO was 8.7% and did not significantly differ from patients without heterotaxy. Late deaths were caused by congestive heart failure or pulmonary thromboembolism. The main non-lethal complication was arrhythmia. Patients have significantly improved their functional class at followup. The independent risk factor for lethal outcomes after BCPA and MFO was preoperative regurgitation at atrioventricular valves (P=0.012). BCPA and MFO in patients with a functionally single ventricle and heterotaxy syndrome allow to significantly improves their quality of life. Preoperative regurgitation at atrioventricular valves worsens surgical results. © 2011 Published by European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: adolescent; adult; article; atrioventricular block; bidirectional cavopulmonary anastomosis; cause of death; cavopulmonary connection; child; congestive heart failure; controlled study; follow up; Fontan procedure; heart arrhythmia; heart single ventricle; heart valve regurgitation; heterotaxy syndrome; human; intermethod comparison; kidney failure; liver failure; major clinical study; modified Fontan operation; mortality; pleura effusion; pneumonia; postoperative complication; preschool child; priority journal; quality of life; risk factor; sepsis; supraventricular tachycardia; surgical infection; surgical risk; surgical technique

Contemporary management of congenital malformations of the heart in infants with Ellis - Van Creveld syndrome: A report of nine cases - O'Connor, M.J.; Rider, N.L.; Thomas Collins II, R.; Hanna, B.D.; Holmes Morton, D.; Strauss, K.A. (Cardiology in the Young, 2011)
Ellis - van Creveld syndrome is an autosomal recessive disorder manifest by short-limb dwarfism, thoracic dystrophy, postaxial polydactyly, dysplastic nails and teeth, and an approximately 60% incidence of congenital malformations of the heart. Despite patients with Ellis - van Creveld syndrome being regarded as having a high surgical risk, few data are available regarding their outcomes following surgery for congenital malformations of the heart in the current era. Materials and methods: In this retrospective report, we summarise the clinical observations and outcomes of nine infants with Ellis - van Creveld syndrome who underwent surgery for congenital malformations of the heart between 2004 and 2009. Results: We identified 15 patients with Ellis - van Creveld syndrome during the study period; 11 (73%) had haemodynamically significant congenital malformations of the heart warranting surgery. In two of these patients, surgery was not performed. Of the nine patients who underwent surgery, all of whom were infants, eight (89%) had various forms of an atrioventricular septal defect and one patient (11%) had hypoplastic left heart syndrome (mitral and aortic atresia). Among the nine patients who underwent surgery, four (44%) died at a median of 102 days with a range of 25-149 days post-operatively, mostly from respiratory failure. Respiratory morbidity was seen in all surviving patients, of whom three underwent tracheostomy. Conclusions: Surgery for congenital malformations of the heart can be successful in infants with Ellis - van Creveld syndrome, but mortality is high and post-operative respiratory morbidity should be expected. © Copyright Cambridge University Press 2010.
Keywords: aorta valve atresia; aortic valve disease; article; cause of death; clinical article; disease association; Ellis van Creveld syndrome; heart atrium septum defect; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; infant; mitral valve atresia; newborn morbidity; outcome assessment; postoperative period; respiratory failure; retrospective study; surgical mortality; survival time; tracheostomy; treatment indication

Neurobehavioral abnormalities in newborns with congenital heart disease requiring open-heart surgery - Massaro, A.N.; Glass, P.; Brown, J.; Chang, T.; Krishnan, A.; Jonas, R.A.; Donofrio, M.T. (Journal of Pediatrics, 2011)
In a prospective study, we evaluated the perioperative application of the Neonatal Intensive Care Unit Network Neurobehavioral Scale in a cohort of newborns with congenital heart disease (CHD). Infants with CHD were found to have suboptimal neurobehavioral performance compared with healthy infants without CHD, with particular vulnerability in the Regulation and Stress subscales. Copyright © 2011 Mosby Inc. All rights reserved.
Keywords: Apgar score; article; behavior disorder; birth weight; cesarean section; cohort analysis; congenital heart disease; controlled study; deep hypothermic circulatory arrest; female; gestational age; head circumference; heart single ventricle; human; hypoplastic left heart syndrome; intensive care unit; major clinical study; male; newborn; open heart surgery; prenatal diagnosis; priority journal; risk factor

Impact of oral sildenafil on exercise performance in children and young adults after the fontan operation: A randomized, double-blind, placebo-controlled, crossover trial - Goldberg, D.J.; French, B.; McBride, M.G.; Marino, B.S.; Mirarchi, N.; Hanna, B.D.; Wernovsky, G.; Paridon, S.M.; Rychik, J. (Circulation, 2011)
Background-: Children and young adults with single-ventricle physiology have abnormal exercise capacity after the Fontan operation. A medication capable of decreasing pulmonary vascular resistance should allow improved cardiac filling and improved exercise capacity. Methods and results-: This study was a double-blind, placebo-controlled, crossover trial conducted in children and young adults after Fontan. Subjects were randomized to receive placebo or sildenafil (20 mg three times daily) for 6 weeks. After a 6-week washout, subjects crossed over for an additional 6 weeks. Each subject underwent an exercise stress test at the start and finish of each phase. After taking sildenafil, subjects had a significantly decreased respiratory rate and decreased minute ventilation at peak exercise. At the anaerobic threshold, subjects had significantly decreased ventilatory equivalents of carbon dioxide. There was no change in oxygen consumption during peak exercise, although there was a suggestion of improved oxygen consumption at the anaerobic threshold. Improvement at the anaerobic threshold was limited to the subgroup with single left or mixed ventricular morphology and to the subgroup with baseline serum brain natriuretic peptide levels 100 pg/mL. Conclusions-: In this cohort, sildenafil significantly improved ventilatory efficiency during peak and submaximal exercise. There was also a suggestion of improved oxygen consumption at the anaerobic threshold in 2 subgroups. These findings suggest that sildenafil may be an important agent for improving exercise performance in children and young adults with single-ventricle physiology after the Fontan operation. © 2011 American Heart Association, Inc.
Keywords: brain natriuretic peptide; carbon dioxide; oxygen; placebo; sildenafil; abdominal pain; adolescent; adult; anaerobic threshold; article; clinical article; constipation; crossover procedure; double blind procedure; exercise; female; flushing; Fontan procedure; headache; human; lung capacity; male; oxygen consumption; priority journal; protein blood level; randomized controlled trial; side effect; revatio

Impact of age at fontan completion on functional status at mid-term follow up - Lytrivi, I.D.; Sfyridis, P.G.; Papagiannis, J.; Kirvassilis, G.; Zavaropoulos, P.; Sarris, G.E. (Hellenic Journal of Cardiology, 2011)
Introduction: Although the Fontan palliation is now being applied to younger patients, the influence of patients' age at the time of surgery on mid- and long-term results remains unclear. It has been our policy to perform Fontan operations when patients are around 5 years old in order to fit a larger conduit and minimize the risk of later obstruction. We sought to investigate whether age at Fontan completion affects subsequent clinical status in patients followed up for more than 3 years. Methods: We carried out a cross-sectional study of Fontan patients who underwent total cavopulmonary connection between 1997 and 2009 and were followed up for ≥3 years with detailed chart review, ECG, echocardiogram, and functional status questionnaire. Results: Of the total of 58 patients there were 56 long-term survivors. Of these, 41 had undergone surgery ≥3 years prior to the time of the study. We were able to contact 37 patients, who comprised our study cohort (mean follow up 6.3, range 3.0-11.0 years). Mean age at operation was 7.4 years (median 5.5, range 3.0-29.5 years). At latest follow up, 97% were in NYHA class I or II. In terms of somatic development, 21% (8/37) for weight and 19% (7/37) for height were below the 25th percentile for age-matched controls. Excluding one patient with developmental delay due to an underlying syndrome, there were 5 patients (13.5%) with mild learning disabilities and one with moderate delays. No additional surgeries had been performed. Tissue Doppler imaging measurements of systolic and diastolic velocities of the lateral annulus of the dominant ventricle revealed abnormalities of both systolic function and diastolic compliance, although qualitatively the systolic function of the single ventricle was considered adequate in all patients. Conclusions: Although earlier Fontan palliation is considered beneficial in the long term from the viewpoint of exercise capacity and hemodynamics, even late Fontan completion provides acceptable mid-term results in terms of the patients' functional status.
Keywords: adolescent; adult; age; article; body height; body weight; cavopulmonary connection; child; clinical article; controlled study; developmental disorder; diastolic blood pressure; echocardiography; electrocardiogram; female; follow up; Fontan procedure; functional status; human; learning disorder; male; medical record review; physical development; preschool child; questionnaire; school child; systolic blood pressure; tissue Doppler imaging

Congenital heart defects in Europe: Prevalence and perinatal mortality, 2000 to 2005 - Dolk, H.; Loane, M.; Garne, E. (Circulation, 2011)
Background- This study determines the prevalence of Congenital Heart Defects (CHD), diagnosed prenatally or in infancy, and fetal and perinatal mortality associated with CHD in Europe. Methods and Results- Data were extracted from the European Surveillance of Congenital Anomalies central database for 29 population-based congenital anomaly registries in 16 European countries covering 3.3 million births during the period 2000 to 2005. CHD cases (n=26 598) comprised live births, fetal deaths from 20 weeks gestation, and terminations of pregnancy for fetal anomaly (TOPFA). The average total prevalence of CHD was 8.0 per 1000 births, and live birth prevalence was 7.2 per 1000 births, varying between countries. The total prevalence of nonchromosomal CHD was 7.0 per 1000 births, of which 3.6% were perinatal deaths, 20% prenatally diagnosed, and 5.6% TOPFA. Severe nonchromosomal CHD (ie, excluding ventricular septal defects, atrial septal defects, and pulmonary valve stenosis) occurred in 2.0 per 1000 births, of which 8.1% were perinatal deaths, 40% were prenatally diagnosed, and 14% were TOPFA (TOPFA range between countries 0% to 32%). Live-born CHD associated with Down syndrome occurred in 0.5 per 1000 births, with >4-fold variation between countries. Conclusion- Annually in the European Union, we estimate 36 000 children are live born with CHD and 3000 who are diagnosed with CHD die as a TOFPA, late fetal death, or early neonatal death. Investing in primary prevention and pathogenetic research is essential to reduce this burden, as well as continuing to improve cardiac services from in utero to adulthood. Copyright © 2011 American Heart Association. All rights reserved.
Keywords: aortic coarctation; aortic valve stenosis; arterial trunk; article; Austria; Belgium; birth rate; congenital heart malformation; Croatia; Denmark; Down syndrome; Ebstein anomaly; Europe; Fallot tetralogy; fetus; fetus death; fetus malformation; fetus mortality; France; Germany; gestational age; great vessels transposition; heart disease; heart single ventricle; human; hypoplastic right heart; infant; Ireland; Italy; live birth; major clinical study; Malta; Netherlands; Norway; perinatal mortality; perinatal period; Poland; pregnancy outcome; pregnancy termination; prenatal diagnosis; prevalence; priority journal; pulmonary valve atresia; pulmonary valve stenosis; Spain; survival; Switzerland; tricuspid valve atresia; trisomy 13; trisomy 18; Ukraine; United Kingdom

Longitudinal findings from a Norwegian case-cohort study on internalizing problems in children with congenital heart defects - Stene-Larsen, K.; Brandlistuen, R.E.; Holmstrøm, H.; Landolt, M.A.; Eskedal, L.T.; Engdahl, B.; Vollrath, M.E. (Acta Paediatrica, International Journal of Paediatrics, 2011)
Aim: To examine the association of the severity of congenital heart defects (CHDs) with internalizing problems in 18-month-olds and to explore the extent to which the internalizing problems are influenced by maternal distress and emotional reactivity in the child at age 6 months. Methods: We linked prospective data from the Norwegian Mother and Child Cohort Study, conducted by the Norwegian Institute of Public Health, with a nationwide CHD registry and identified 198 18-month-olds with CHDs in a cohort of 47 692 toddlers. Maternal reports on the children's emotional reactivity at age 6 months, the children's internalizing problems (anxiety, sleep problems, emotional reactivity) at age 18 months and maternal distress were assessed by questionnaires. Results: We found an association at age 18 months between the severity of the CHD and anxiety but not sleep problems or emotional reactivity. Children with severe but not with mild or moderate CHDs were twice as likely to experience the symptoms of anxiety compared with controls. These symptoms are not merely sequelae of earlier psychological reactions or concurrent maternal distress. Conclusion: Should these findings be replicated, future studies ought to investigate the mechanisms leading to elevated anxiety in toddlers with CHDs. In addition, clinical interventions should address the child's anxiety as well as the interaction between the parents and the child. © 2010 Foundation Acta Pædiatrica.
Keywords: anxiety disorder; aortic coarctation; aortic stenosis; article; asthma; birth weight; brain malformation; child; chylothorax; cleft lip; cleft palate; congenital heart malformation; controlled study; diabetes mellitus; disease severity; distress syndrome; emotion; esophagus atresia; Fallot tetralogy; female; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; hemangioma; human; hydrocephalus; hypoplastic left heart syndrome; infant; intestine malformation; limb malformation; lung vein drainage anomaly; male; maternal welfare; micrognathia; mood; neoplasm; Norway; patent ductus arteriosus; patent foramen ovale; prematurity; preschool child; priority journal; pulmonary subvalvular stenosis; pulmonary valve atresia; sleep disorder; spherocytosis; temperament

The severe end of the spectrum: Hypoplastic left heart in Potocki-Lupski syndrome - Sanchez-Valle, A.; Pierpont, M.E.; Potocki, L. (American Journal of Medical Genetics, Part A, 2011)
Potocki-Lupski syndrome (PTLS) is a recently described microduplication syndrome associated with duplication 17p11.2, including the RAI1 gene. Features of PTLS include hypotonia, feeding difficulties, failure to thrive, developmental delay and behavioral abnormalities including autistic spectrum disorder, anxiety, and inattention. Cardiovascular anomalies were not recognized as a feature of duplication 17p11.2 until 2007 when noted in over 50% of a clinically characterized cohort. We report a patient with hypoplastic left heart syndrome whose diagnosis of PTLS was delayed until a genetic evaluation at age 4 years because of severe expressive language impairment. We suggest that array comparative genomic hybridization be performed in infants with severe congenital heart defects. © 2011 Wiley-Liss, Inc.
Keywords: article; borderline hypertension; case report; child; chromosome 17p; chromosome analysis; chromosome duplication; delayed diagnosis; developmental disorder; disease severity; echocardiography; face dysmorphia; genetic analysis; genetic disorder; heart transplantation; human; hypoplastic left heart syndrome; language disability; male; muscle hypotonia; periodic limb movement disorder; Potocki Lupski syndrome; priority journal; school child

Prevention of postoperative pericardial adhesions in children with hypoplastic left heart syndrome - Salminen, J.T.; Mattila, I.P.; Puntila, J.T.; Sairanen, H.I. (Interactive Cardiovascular and Thoracic Surgery, 2011)
Reoperations for congenital cardiac defects are associated with an increased surgical risk due to adhesions. We compared the capability of a polytetrafluoroethylene (PTFE) membrane, synthetic polyethyleneglycol hydrogel (PEG), and a combination of them to prevent postoperative pericardial adhesions in patients with hypoplastic left heart syndrome (HLHS). Eighteen consecutive patients with HLHS were included. At the end of the Norwood I operation the cranial and the caudal half of the heart of each patient was randomized to receive a PTFE membrane, a synthetic PEG, a combination of them, or no treatment (control). Tenacity and density of adhesions, epicardial visibility, and adhesions between the heart and the sternum were analyzed semiquantitatively at a subsequent bidirectional Glenn operation. The PTFE membrane significantly decreased adhesion formation between the heart and the sternum (P<0.001). However, the PTFE membrane, with or without synthetic PEG, impaired epicardial visibility (P<0.05) when compared to synthetic PEG or controls. Synthetic PEG alone did not significantly reduce the formation of pericardial adhesions. Tenacity and density of adhesions were not affected by any of the treatment modalities. The PTFE membrane significantly decreases postoperative adhesions between the heart and the sternum, but impairs epicardial visibility. Synthetic PEG does not prevent formation of pericardial adhesions. © 2011 Published by European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: macrogol; polytetrafluoroethylene; article; child; clinical article; clinical effectiveness; endoprosthesis; feasibility study; Glenn shunt; heart surgery; human; hydrogel; hypoplastic left heart syndrome; Norwood procedure; patient safety; pericardium adhesion; postoperative complication; priority journal; randomized controlled trial; risk reduction; surgical approach; surgical technique; tissue adhesion

Factors associated with the physical activity level of children who have the Fontan procedure - Longmuir, P.E.; Russell, J.L.; Corey, M.; Faulkner, G.; McCrindle, B.W. (American Heart Journal, 2011)
Background: Children with complex heart defects are sedentary, with activity level unrelated to exercise capacity. We sought to identify factors associated with physical activity level for children who have the Fontan procedure. Methods: We used a cross-sectional study, 64 children (25 female, 5-11 years) after Fontan. Measurements were weekly minutes of moderate-to-vigorous physical activity, cardiac status, resting/exercise cardiopulmonary capacity, gross motor skill, health-related endurance/strength/ body composition, and parent/child activity perceptions. Results: Participants performed 361 ± 137 minutes per week of moderate-to-vigorous physical activity. Increased activity related to antithrombotic medication use (86 min/wk), lower resting heart rate (3 min/wk), higher weekday outdoor time (0.7 minutes per outside minute), lower family income (13 minutes per $10,000), and higher parent rating of child's activity relative to peers (36 min/wk). Factors related to decreased activity were winter season (-84 min/wk), history of arrhythmia (-96 min/wk), and greater child confidence in own ability to be active (-113 min/wk). Conclusions: Physical activity after the Fontan procedure is primarily associated with factors unrelated to cardiac status. Interventions that impact these modifiable factors would be expected to enable these children to achieve the recommended activity levels associated with optimal health. © 2011 Mosby, Inc.
Keywords: antithrombocytic agent; article; body composition; child; cross-sectional study; endurance; exercise; family; female; Fontan procedure; health status; heart arrhythmia; heart function; heart rate; human; income; major clinical study; male; motor performance; parent; peer group; perception; physical activity; preschool child; priority journal; rating scale; school child; strength; winter

Disturbance of glucose homeostasis after pediatric cardiac surgery - Verhoeven, J.J.; Hokken-Koelega, A.C.S.; Den Brinker, M.; Hop, W.C.J.; Van Thiel, R.J.; Bogers, A.J.J.C.; Helbing, W.A.; Joosten, K.F.M. (Pediatric Cardiology, 2011)
This study aimed to evaluate the time course of perioperative blood glucose levels of children undergoing cardiac surgery for congenital heart disease in relation to endogenous stress hormones, inflammatory mediators, and exogenous factors such as caloric intake and glucocorticoid use. The study prospectively included 49 children undergoing cardiac surgery. Blood glucose levels, hormonal alterations, and inflammatory responses were investigated before and at the end of surgery, then 12 and 24 h afterward. In general, blood glucose levels were highest at the end of surgery. Hyperglycemia, defined as a glucose level higher than 8.3 mmol/l (>150 mg/dl) was present in 52% of the children at the end of surgery. Spontaneous normalization of blood glucose occurred in 94% of the children within 24 h. During surgery, glucocorticoids were administered to 65% of the children, and this was the main factor associated with hyperglycemia at the end of surgery (determined by univariate analysis of variance). Hyperglycemia disappeared spontaneously without insulin therapy after 12-24 h for the majority of the children. Postoperative morbidity was low in the study group, so the presumed positive effects of glucocorticoids seemed to outweigh the adverse effects of iatrogenic hyperglycemia. © 2010 The Author(s).
Keywords: dexamethasone; glucocorticoid; glucose; hydrocortisone; insulin; interleukin 10; interleukin 6; lactic acid; methylprednisolone; stress hormone; adolescent; adult; article; blood glucose monitoring; caloric intake; child; child health; clinical article; clinical evaluation; congenital heart disease; controlled study; coronary artery anomaly; disease course; drug effect; drug use; Fallot tetralogy; female; glucose blood level; glucose homeostasis; heart atrium septum defect; heart left ventricle outflow tract obstruction; heart right ventricle outflow tract obstruction; heart single ventricle; heart ventricle septum defect; hormone synthesis; human; hyperglycemia; iatrogenic disease; infant; insulin blood level; male; mitral valve regurgitation; open heart surgery; pediatric surgery; postoperative complication; preschool child; school child

Pathology of the aortic arch in hypoplastic left heart syndrome: Surgical implications - Sivanandam, S.; MacKey-Bojack, S.M.; Moller, J.H. (Pediatric Cardiology, 2011)
Aortic arch reconstruction plays an important role in the success of the Norwood procedure (NP) for hypoplastic left heart syndrome (HLHS). This study investigated the cardiac specimens to determine the etiology of distal aortic arch obstruction after the NP for HLHS and to locate coarctation of the aorta in HLHS untreated by surgery. This study examined 17 cardiac specimens: 9 that had NP and 8 not treated by surgery. The findings after NP showed frequent failure to resect the coarctation segment completely and failure to extend the augmentation patch into the descending aorta. Five (62.5%) of the eight hearts not treated by surgery had significant periductal coarctation of the aorta. After NP for nine patients, three (33%) had residual coarctation of the aorta. To minimize the risk of recurrent or persistent aortic arch obstruction after NP and to improve the long- and short-term outcome, the ductal tissue and the coarctation segment encircling the aortic lumen should be resected. The distal wall incision should be extended at least 5 mm beyond the distal aspect of the ductal tissue. These steps could avoid major aortic arch obstruction, promote growth of the native aortic tissue, and avoid ventricular dysfunction. © 2010 Springer Science+Business Media, LLC.
Keywords: aortic arch syndrome; aortic coarctation; aortic stenosis; aortic arch surgery; article; controlled study; descending aorta; disease severity; fetus; heart right ventricle hypertrophy; heart ventricle septum defect; histopathology; human; human tissue; hypoplasia; hypoplastic left heart syndrome; infant; mitral valve atresia; mitral valve stenosis; Norwood procedure; outcome assessment; pulmonary vein malformation; recurrent disease; risk reduction

Grandparents and siblings of children with congenital heart disease - Ravindran, V.P.; Rempel, G.R. (Journal of Advanced Nursing, 2011)
Aim: This paper is a report of a study of the process of grandparent involvement with siblings of preschool children with hypoplastic left heart syndrome. Background: An increasing number of grandparents are involved in parental or near-parental roles with their grandchildren. Most research concerns grandparent involvement due to parental issues (e.g. teenage pregnancy, mental illness, addiction). Some research addresses grandparent involvement when their grandchild is ill. Grandparents''double concern' for both their adult children and their ill grandchildren is reported in the literature. In this paper, we describe a third concern for grandparents: the sibling(s) of their sick grandchild. Method: Individual interviews were conducted in 2007 with 15 grandparents of six preschool children with complex congenital heart disease. Open and selective coding, categorization, and theoretical memoing were used to analyse the data. Findings: 'Stepping in as needed' and 'safeguarding relationships' were identified as two core categories related to grandparenting siblings of children with heart disease. Grandparents stepped into a parent role with toddler and preschool-aged siblings by attending to their daily care routines, recreational and play times, and relational needs while parents were occupied with their sick and hospitalized infants. Grandparents' concerted efforts to sustain parent-child and child-sibling relationships were also striking. Conclusion: Our findings extend the concept of 'double concern' to 'triple concern', and direct a research and practice focus towards the unexplored roles and needs of grandparents and siblings in families whose young children have life-threatening illnesses. © 2010 The Authors. Journal of Advanced Nursing © 2010 Blackwell Publishing Ltd.
Keywords: adolescent; adult; aged; article; child; child care; child parent relation; family health; family size; female; home care; human; human relation; hypoplastic left heart syndrome; infant; male; middle aged; organization and management; pregnancy; preschool child; psychological aspect; qualitative research; role playing; sibling

Ventricular performance in long-term survivors after fontan operation - Nakamura, Y.; Yagihara, T.; Kagisaki, K.; Hagino, I.; Kobayashi, J. (Annals of Thoracic Surgery, 2011)
Background Ventricular function and arrhythmia in patients with Fontan circulation in long-term follow-up are still unknown. Methods We retrospectively reviewed 48 patients who survived and were followed up for more than 15 years, among 110 patients who underwent Fontan operation in our institute from 1979 to 1992. Atriopulmonary connection was performed in 26 patients and total cavopulmonary connection in 22. The patients were categorized into right ventricle, left ventricle, and biventricle groups. Follow-up cardiac catheterization and exercise test were performed routinely every 5 years post surgery. Median age at Fontan operation was 5 years. Results Mean follow-up was 18.5 years. Cardiac index in the total cavopulmonary connection group was higher than in the atriopulmonary connection group at 10 and 15 years post surgery (p < 0.05). Ejection fraction in the left-ventricle group was higher than in the right-ventricle group. End-diastolic volume at 5, 10, and 15 years was significantly lower than at 1 year (p < 0.05). End-diastolic pressure at 10 years was significantly higher than at 1 and 5 years (p < 0.05). Beyond 15 years, 6 patients developed ventricular tachycardia. The only significant risk factors for the onset of ventricular tachycardia in a multivariate analysis were age at Fontan operation and absolute age (p < 0.05). Conclusions Long-term follow-up of patients demonstrated that postoperative ventricular systolic performance seemed to become steady. Ventricular tachycardia was detected 15 years post surgery, especially in older patients with older age at Fontan operation, possibly revealing a risk factor in the long-term postoperative period, thereby meriting further consideration. © 2011 The Society of Thoracic Surgeons.
Keywords: adolescent; adult; article; atriopulmonary connection; cardiopulmonary function; cavopulmonary connection; child; clinical article; exercise test; female; follow up; Fontan procedure; heart catheterization; cardiac index; heart left ventricle; heart left ventricle ejection fraction; heart left ventricle enddiastolic pressure; heart left ventricle enddiastolic volume; heart right ventricle; heart ventricle function; heart ventricle tachycardia; human; long term care; male; preschool child; priority journal; risk assessment; school child; survivor; task performance

Clinical profile of the adolescent/adult fontan survivor - Pike, N.A.; Evangelista, L.S.; Doering, L.V.; Koniak-Griffin, D.; Lewis, A.B.; Child, J.S. (Congenital Heart Disease, 2011)
Objectives. The study aims to describe the clinical profile of the adult Fontan survivor and identify the worries, symptoms, and the impact of cardiac surveillance most commonly experienced. Design. A descriptive, cross-sectional design was used. Setting. The study was performed in outpatient adult and pediatric cardiology clinics in university-affiliated and private practice offices. Patients. Fifty-four adolescent and adult patients with single ventricle congenital heart disease who have undergone the Fontan procedure participated in the study. The mean age was 26 ± 9 years with 52% female and 63% Caucasian. Outcome Measures. Demographic and clinical data were obtained by a standard intake form and retrospective chart reviews. The Congenital Heart Disease TNO/AZL Adult Quality Of Life questionnaire was completed to assess worries, symptoms, and the impact of cardiac surveillance. Results. The majority were single (73%), employed or full-time students (93%), with health insurance (94%), had a single left ventricle (78%), the diagnosis of tricuspid atresia or double inlet left ventricle (59%), lateral tunnel Fontan type (44%), history of arrhythmias (76%), left ventricle ejection fraction percentage >50 (66%), oxygen saturations >90% (70%), frequent headaches (50%), scoliosis (22%), varicose veins, ascites, and liver cirrhosis (46%), normal body mass index (59%), and New York Heart Association class I (48%) and II-III (52%). Primary worries related to current health (83%), job/employment (69%), ability to work, (61%) and living independently (54%). The most bothersome symptoms were shortness of breath with ambulation (69%), dizziness (61%), and palpitations (61%). Conclusions. Fontan survivors experience residua and sequelae from multiple surgical procedures and the natural disease course. Our results support the need for ongoing assessment of both physical symptoms and psychosocial concerns, and suggest the need for multiple risk factor intervention strategies that improve physical and emotional health in Fontan survivors © 2011 Copyright the Authors. Congenital Heart Disease © 2011 Wiley Periodicals, Inc.
Keywords: adolescent; adult; article; ascites; cross-sectional study; female; Fontan procedure; headache; heart arrhythmia; heart left ventricle ejection fraction; heart single ventricle; human; liver cirrhosis; major clinical study; male; outpatient; oxygen saturation; priority journal; psychosocial care; quality of life; questionnaire; scoliosis; survivor; symptomatology; tricuspid valve atresia; varicosis

Management of pregnancy in patients with congenital heart disease - Harris, I.S. (Progress in Cardiovascular Diseases, 2011)
Congenital heart diseases are the most common birth defects in humans, affecting approximately 0.8% of all live births. In the past, many of the more severe defects resulted in profound disability and death during childhood, and adult survival was exceptional. The past 4 decades have seen dramatic improvements in the survival and quality of life of patients with the more severe defects. As a result of these improvements, the challenges of caring for adults with congenital heart disease are only now being realized. Most women with congenital heart disease are now expected to reach childbearing age and maternal cardiac disease is the major cause of maternal morbidity and mortality. As such, appropriate pre-pregnancy counseling and management during pregnancy are fundamental components of the care of these patients. This article describes the circulatory changes that occur during normal pregnancy and delivery, addresses the risks posed during pregnancy by specific congenital lesions, and reviews the current data on pregnancy outcomes in patients with individual congenital defects. © 2011 Elsevier Inc.
Keywords: antibiotic agent; heparin; warfarin; antibiotic prophylaxis; anticoagulant therapy; aortic coarctation; aortic disease; aortic stenosis; article; cardiovascular response; clinical assessment; congenital heart disease; cyanotic heart disease; drug efficacy; drug safety; drug substitution; drug withdrawal; embryotoxicity; endocarditis; Fallot tetralogy; fetus echography; fetus risk; first trimester pregnancy; Fontan procedure; heart atrium septum defect; heart hemodynamics; heart ventricle septum defect; high risk pregnancy; human; labor; low drug dose; maternal care; maternal mortality; patient counseling; pregnancy; pregnancy complication; pregnancy disorder; puerperium; pulmonary artery stenosis; risk assessment; second trimester pregnancy; third trimester pregnancy; thrombosis; tricuspid valve atresia

Self perception and quality of life of adolescents who had undergone open-heart surgery due to cyanotic congenital heart disease in their infancy - Yildiz, C.E.; Zahmacioǧlu, O.; Koca, B.; Oktay, V.; Gökalp, S.; Eroǧlu, A.G.; Çetin, G.; Öztunç, F. (Turk Pediatri Arsivi, 2011)
Aim: To assess together with their parents, the quality-of-life of the teenage patients who had undergone open heart surgery because of cyanotic heart disease during their infancy and to compare their self-perception to that of physically healthy control group. Material and Method: This study includes 53 patients who had undergone operation for cyanotic congenital heart disease in Istanbul University, Institute of Cardiology, between 1989-1994. The relatives and the patients were informed with a consent form approved by Istanbul University, Cerrahpaşa Medical Faculty, Clinical Studies, Ethics Commitee (Decree no. D-005, Date: 11-10-2009). Group 1 was the healthy control group (15 patients, median age: 19 years, 8 months), Group 2 included patients with single ventricle who had undergone Fontan procedure (20 patients, median age: 19 years, 6 months; 10 of them had tricuspid atresia, five of them had pulmonary atresia with intact ventricular septum, three of them had double inlet left ventricle, one of them had double outlet right ventricle, one of them had ventricular septal defect and pulmonary atresia), group 3 included patients who had undergone operation for congenital cyanotic heart disease (33 patients, median age: 19 years, 2 months; 18 of them had transposition of the great arteries, 10 of them had tetralogy of Fallot, two of them had complete atrioventricular canal defect and pulmonary stenosis, two of them had double outlet right ventricle, one of them had pentalogy of Fallot). In this study, the quality of life and self perception scales were used. Quality of life scale was filled by patients, healthy adolescents and their parents separately. Self perception scale was only filled by patients and healthy adolescents. The comparison of age and self perception scores between the groups was carried out with unidirectional Analysis of variance (ANOVA) and the multicomparisons with LSD (Least Significant Difference). Since the quality of life variable does not have a normal distribution, the comparions were carried out with Kruskal-Wallis nonparametric ANOVA test and the multicomparisons with Dunn's test. Results: There was not a significant difference between the groups in terms of age and sex. In the quality of life scale (QOLS), for the replies to related questions, a significant difference was determined between the groups. The replies of group 2 and 3 for about quality of life of both children and the parents were far more negative when compared to those of the control group. When the groups were compared via multiple comparison tests, there was no significant difference between group 2 and 3. The replies of the parents regarding their children's quality of life, were statistically more negative than those of their children (p<0.001). Within the self perception scale, between group 1 and 3, there were significant differences about the social acceptance, behaviours in relationships and general self perception (p=0.03, p=0.03 and p=0.01; respectively). The most significant difference that was detected between group 1 and 2, was about the behaviour in relationships (p=0.04). Conclusions: With the help of developing technology, and surgical experience, many complex cyanotic heart diseases are treated successfully and most patients reach puberty. However the responses for quality of life and self perception paremeters of this group of patients are more negative than those of the control group. Therefore, these adolescents and especially their parents may need psychosocial support.
Keywords: adolescent; adult; article; controlled study; cyanotic heart disease; endocardial cushion defect; fallot pentalogy; Fallot tetralogy; Fontan procedure; great vessels transposition; heart left ventricle double inlet; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; human; human relation; major clinical study; open heart surgery; pediatric surgery; pulmonary valve atresia; pulmonary valve stenosis; quality of life; rating scale; self concept; social behavior; social interaction; tricuspid valve atresia; Turkey (republic); university hospital

Ischemic myocardial injuries after cardiac malformation repair in infants may be associated with oxidative stress mechanisms - Oliveira, M.S.; Floriano, E.M.; Mazin, S.C.; Martinez, E.Z.; Vicente, W.V.A.; Peres, L.C.; Rossi, M.A.; Ramos, S.G. (Cardiovascular Pathology, 2011)
Background: Despite advances in pediatric cardiac surgery, perioperative myocardial injury can be the major determinant of postoperative dysfunction after cardiac surgery. This study investigated the pathology-related differences in 29 infants with congenital heart disease that led to death. The infants were treated at the University Hospital of Ribeirão Preto, Brazil. Methods: The patients were divided into four groups: Group 1, 16 infants who underwent operations for congenital heart disease on cardiopulmonary bypass; Group 2, four infants who underwent off-cardiopulmonary bypass operations for congenital heart disease; Group 3, nine infants who died from congenital heart disease prior to surgical treatment; and Group 4 (control group), five infants with no congenital heart disease and who died from other causes. The myocardial injuries and oxidative stress mechanisms were assessed by histopathology and immunohistochemistry and were quantified by morphometrical analyses. Results: Contraction band necrosis and dystrophic calcification were found primarily in infants of Group 1. Coagulation necrosis and healing were prominent in Group 2, while infants without repair (Group 3) showed mainly colliquative myocytolysis. Apoptotic cells were more prominent in the operative groups. The control group showed no significant myocardial lesions. Lipid peroxidation was the principal mechanism of oxidative stress accounting for the myocardial lesions. Conclusion: The diversity of the lesions observed in these hearts seemed to indicate a large spectrum of cell damage due to inadequate myocardial perfusion, especially when these infants underwent surgery. Oxidative mechanisms could be a common mediator in the pathogenesis of myocardial injuries, mediated by peroxidation of the membrane phospholipids and resulting in changes in the permeability of the cell membrane, cell death, and intracellular calcium overload. Furthermore, an immature and often hypertrophied myocardium may promote unfavorable conditions, leading to heart failure and a lethal outcome. © 2011 Elsevier Inc. All rights reserved.
Keywords: calcium; membrane phospholipid; anencephalus; aortic arch interruption; aortic coarctation; aortic occlusion; apoptosis; article; bicuspid aortic valve; brain edema; Brazil; calcinosis; calcium cell level; cardiopulmonary bypass; cell damage; cell death; cell membrane permeability; child death; clinical article; congenital heart malformation; controlled study; cytolysis; dextrocardia; disease association; encephalitis; Fallot tetralogy; female; great vessels transposition; heart atrium septum defect; cardiac muscle cell; heart muscle ischemia; heart muscle perfusion; heart right ventricle double outlet; heart single ventricle; heart surgery; heart ventricle septum defect; histopathology; human; human tissue; hypoplastic left heart syndrome; immunohistochemistry; infant; lipid peroxidation; lung hypoplasia; male; mitral valve atresia; morphometry; newborn; oxidative stress; patent ductus arteriosus; patent foramen ovale; persistent left superior vena cava; priority journal; protein calorie malnutrition; pulmonary valve atresia; pulmonary valve stenosis; sex difference; wound healing

Comorbid psychopathology factor structure on the Baby and Infant Screen for Children with aUtIsm Traits-Part 2 (BISCUIT-Part 2) - Matson, J.L.; Boisjoli, J.A.; Hess, J.A.; Wilkins, J. (Research in Autism Spectrum Disorders, 2011)
Autism Spectrum Disorders (ASD) is a topic receiving great attention from researchers and clinicians in the field. However, many of these studies focus on children or adults, with research on infants and toddlers evincing ASD being virtually non-existent. Even more scant is information pertaining to the assessment of symptoms of comorbid psychopathology in this young population. Nonetheless, it is essential to identify comorbid conditions in addition to the symptoms associated with the core features of ASD. Building on the effectiveness of early intervention with children with ASD, comprehensive evaluations and individualized treatment goals are necessary and may enhance treatment efficacy. The Baby and Infant Screen for Children with aUtIsm Traits-Part 2 (BISCUIT-Part 2) is a new assessment, specifically designed to examine symptoms of psychopathology in infants and toddlers with ASD. The purpose of this study was twofold. First, the factor structure of the BISCUIT-Part 2 was established. Second, group differences in the endorsement of symptoms of psychopathology were examined between infants and toddlers with and without ASD. © 2011 Elsevier Ltd.
Keywords: article; asthma; cerebral palsy; child; comorbidity; controlled study; corpus callosum agenesis; diabetes mellitus; Down syndrome; epilepsy; female; fetal alcohol syndrome; human; hydrocephalus; hypoplastic left heart syndrome; autism; major clinical study; male; meningitis; mental disease; preschool child; priority journal; screening; seizure; spinal dysraphism; symptomatology; traumatic brain injury; Usher syndrome

Deep hypothermic circulatory arrest does not impair neurodevelopmental outcome in school-age children after infant cardiac surgery - Fuller, S.; Rajagopalan, R.; Jarvik, G.P.; Gerdes, M.; Bernbaum, J.; Wernovsky, G.; Clancy, R.R.; Solot, C.; Nicolson, S.C.; Spray, T.L.; Gaynor, J.W. (Annals of Thoracic Surgery, 2010)
Background The purpose of this study was to assess deep hypothermic circulatory arrest (DHCA) as a modifier of neurodevelopmental (ND) outcomes in preschool children after cardiac surgery in infancy for repair of congenital heart defects (CHD). Methods This is a planned analysis of infants enrolled in a prospective study of apolipoprotein E polymorphisms and ND outcome after cardiac surgery. The effect of DHCA was assessed in patients with single or biventricular CHD without aortic arch obstruction. Neurodevelopmental assessment at 4 years of age included cognition, language, attention, impulsivity, executive function, social competence, and visual-motor and fine-motor skills. Patient and procedural variables were evaluated in univariate and multivariate models. Results Neurodevelopmental testing was completed in 238 of 307 eligible patients (78%). Deep hypothermic circulatory arrest was used at the discretion of the surgeon at least once in 92 infants (38.6%) with a median cumulative duration of 36 minutes (range, 1 to 132 minutes). By univariate analysis, DHCA patients were more likely to have single-ventricle CHD (p = 0.013), lower socioeconomic status (p < 0.001), a higher incidence of preoperative ventilation (p < 0.001), and were younger and smaller at the first surgery (p < 0.001). By multivariate analysis, use of DHCA was not predictive of worse performance for any ND outcome. Conclusions In this cohort of children undergoing repair of CHD in infancy, patients who underwent DHCA had risk factors associated with worse ND outcomes. Despite these, use of DHCA for repair of single-ventricle and biventricular CHD without aortic arch obstruction was not predictive of worse performance for any ND domain tested at 4 years of age. © 2010 The Society of Thoracic Surgeons.
Keywords: apolipoprotein E; article; attention; child; clinical assessment; cognition; congenital heart malformation; controlled study; deep hypothermic circulatory arrest; female; genetic polymorphism; groups by age; heart surgery; human; impulsiveness; infant; language; major clinical study; male; motor performance; nervous system development; outcome assessment; preoperative evaluation; preschool child; priority journal; prospective study; risk factor; school child; social competence; social status; surgeon; visuomotor coordination

Influence of birth hospital on outcomes of ductal-dependent cardiac lesions - Bennett, T.D.; Klein, M.B.; Sorensen, M.D.; De Roos, A.J.; Rivara, F.P. (Pediatrics, 2010)
OBJECTIVE: The goal was to determine the effect of birth hospital pediatric cardiac specialty center status and neonatal level of care on 90-day mortality for infants with ductal-dependent congenital heart disease. METHODS: A population-based, retrospective, cohort study was conducted in Washington State in 1987-2006. All infants born in Washington with gestational ages of ≥32 weeks and birth weights of ≥1500 g who were admitted to a Washington hospital for the care of a congenital cardiac anomaly likely to be ductal dependent were included. Subjects were required to receive a surgical or interventional cardiac procedure within 30 days after birth. Birth certificate data were linked with death certificate data and hospital administrative records. The exposures of interest were birth hospital pediatric cardiac specialty center status and neonatal level of care. The primary outcome was death within 90 days. RESULTS: A total of 823 infants met the inclusion criteria, 285 born at specialty centers and 538 at other centers. After adjustment for cardiac diagnoses, other congenital anomalies, birth year, maternal income quartile, and definitive-care hospital, there was no significant difference in 90-day mortality for infants born at specialty centers versus other centers (odds ratio: 1.05 [95% confidence interval: 0.65-1.68]). CONCLUSION: For infants with ductal-dependent congenital heart disease, there was no difference in 90-day mortality for infants born at specialty centers versus other centers in the state of Washington. Copyright © 2010 by the American Academy of Pediatrics.
Keywords: aortic arch interruption; aorta atresia; aortic coarctation; aortic valve stenosis; article; birth weight; cohort analysis; congenital heart disease; ductus arteriosus; esophagus malformation; female; gestational age; great vessels transposition; human; hypoplastic left heart syndrome; infant; infant mortality; intestine malformation; limb malformation; major clinical study; male; newborn care; outcome assessment; priority journal; pulmonary valve atresia; pulmonary valve stenosis; retrospective study; situs inversus; tricuspid valve atresia; trisomy 13; trisomy 18; trisomy 21; Turner syndrome; urinary tract malformation; velocardiofacial syndrome

Parental decision making regarding treatment of hypoplastic left heart syndrome - Ellinger, M.K.; Rempel, G.R. (Advances in Neonatal Care, 2010)
Parents of children diagnosed with a complex congenital heart anomaly such as hypoplastic left heart syndrome (HLHS) are faced with the challenge of choosing the best treatment option for their children. Parents must decide among options of compassionate care, palliative reconstructive surgery, or neonatal cardiac transplantation, and additionally with antenatal diagnosis must decide regarding continuation of pregnancy. With improved survival rates yet persistent morbidities following the Norwood surgical approach for HLHS, controversy remains whether parents should be counseled on all treatment options as evidenced by research that articulates the varied opinions of health care providers. The parents' perspective is less well researched. In this study, interview data from parents who chose the Norwood-Sano surgical option were analyzed to provide insight into the various treatment options they were given following diagnosis of HLHS in their children and how they came to choose the surgical palliation option. Copyright © 2010 by the National Association of Neonatal Nurses.
Keywords: adult; aortic valve; article; child parent relation; decision making; female; heart valve replacement; human; hypoplastic left heart syndrome; male; newborn; parent; pericardium; psychological aspect; pulmonary artery; questionnaire; transplantation

Anthropometric measures after Fontan procedure: Implications for suboptimal functional outcome - Cohen, M.S.; Zak, V.; Atz, A.M.; Printz, B.F.; Pinto, N.; Lambert, L.; Pemberton, V.; Li, J.S.; Margossian, R.; Dunbar-Masterson, C.; McCrindle, B.W. (American Heart Journal, 2010)
Background: Abnormal height and adiposity are observed after the Fontan operation. These abnormalities may be associated with worse functional outcome. Methods: We analyzed data from the National Heart, Lung, and Blood Institute Pediatric Heart Network cross-sectional study of Fontan patients. Groups were defined by height (z-score <-1.5 or ≥-1.5) and body mass index (body mass index [BMI] z-score <-1.5 or -1.5 to 1.5 or ≥1.5). Associations of anthropometric measures with measurements from clinical testing (exercise, echocardiography, magnetic resonance imaging) were determined adjusting for demographics, anatomy, and pre-Fontan status. Relationships between anthropometric measures and functional health status (FHS) were assessed using the Child Health Questionnaire. Results: Mean age of the cohort (n = 544) was 11.9 ± 3.4 years. Lower height-z patients (n = 124, 23%) were more likely to have pre-Fontan atrioventricular valve regurgitation (P = .029), as well as orthopedic and developmental problems (both P < .001). Lower height-z patients also had lower physical and psychosocial FHS summary scores (both P < .01). Higher BMI-z patients (n = 45, 8%) and lower BMI-z patients (n = 53, 10%) did not have worse FHS compared to midrange BMI-z patients (n = 446, 82%). However, higher BMI-z patients had higher ventricular mass-to-volume ratio (P = .03) and lower % predicted maximum work (P = .004) compared to midrange and lower BMI-z patients. Conclusions: Abnormal anthropometry is common in Fontan patients. Shorter stature is associated with poorer FHS and non-cardiac problems. Increased adiposity is associated with more ventricular hypertrophy and poorer exercise performance, which may have significant long-term implications in this at-risk population. © 2010 Mosby, Inc.
Keywords: NCT00132782; brain natriuretic peptide; adolescent; adult; article; body height; body mass; child; cohort analysis; congenital heart disease; echocardiography; exercise test; Fontan procedure; functional assessment; health status; heart valve regurgitation; heart ventricle hypertrophy; heart ventricle volume; hormone blood level; human; major clinical study; nuclear magnetic resonance imaging; postoperative period; preschool child; priority journal; questionnaire; school child; scoring system; short stature; treatment outcome

Growth differentiation factor 15-an early marker of abnormal function of the Fontan circuit in patients with univentricular hearts - Raedle-Hurst, T.M.; Koenigstein, K.; Gruenhage, F.; Raedle, J.; Herrmann, E.; Abdul-Khaliq, H. (American Heart Journal, 2010)
Background: In patients after the Fontan procedure, assessment of ventricular function is difficult and amino-terminal pro-B-type natriuretic peptide levels failed to be directly related to echocardiographic measures of systolic ventricular function. The aim of the study was to evaluate growth differentiation factor 15 (GDF-15), a marker of various stress pathways in the heart and extracardiac tissues. Methods: Plasma GDF-15 levels were measured in 38 consecutive patients after the Fontan procedure and compared to clinical, echocardiographic, and laboratory data; liver tissue stiffness; and venous hepatic flow velocities. Results: Mean GDF-15 levels were 987.2 ± 440.5 pg/mL in patients with an ejection fraction (EF) <50% as compared to 520.2 ± 143.1 pg/mL in those with an EF ≥50% (P < .001). Growth differentiation factor 15 levels were significantly related to the EF of the single ventricle (r = -0.66, P < .001), New York Heart Association functional class (r = 0.43, P = .008), and γGT levels (r = 0.50, P = .002) but weakly to liver tissue stiffness. According to receiver operating characteristic curve analysis, an EF <50% was best predicted by GDF-15 levels (area under the curve [AUC] 0.90, P < .001), peak venous hepatic flow at deep inspiration (AUC 0.89, P = .002), and age at Fontan operation (AUC 0.86, P = .001). Growth differentiation factor 15 and age at Fontan operation proved to be independent predictors in the multivariate analysis. The optimal cutoff of GDF-15 for the prediction of an EF <50% was calculated to be 613 pg/mL with a sensitivity of 90.0% and specificity of 85.7%. Conclusions: Growth differentiation factor 15 might be helpful in detecting early abnormal function of the Fontan circuit in patients with univentricular hearts. In patients with GDF-15 levels exceeding 613 pg/mL, further cardiac evaluation should be considered because impaired systolic function of the single ventricle may be present. © 2010 Mosby, Inc.
Keywords: amino terminal pro brain natriuretic peptide; biological marker; gamma glutamyltransferase; growth differentiation factor 15; adolescent; adult; article; blood flow velocity; child; clinical article; correlation analysis; elastography; female; Fontan procedure; functional assessment; gamma glutamyl transferase blood level; groups by age; heart ejection fraction; heart single ventricle; heart ventricle function; human; liver blood flow; liver fibrosis; male; predictor variable; preschool child; priority journal; protein blood level; receiver operating characteristic; school child; sensitivity and specificity; two dimensional echocardiography; vein blood flow

J. Maxwell Chamberlain Memorial Paper for congenital heart surgery. Deep hypothermic circulatory arrest does not impair neurodevelopmental outcome in school-age children after infant cardiac surgery. - Fuller, S.; Rajagopalan, R.; Jarvik, G.P.; Gerdes, M.; Bernbaum, J.; Wernovsky, G.; Clancy, R.R.; Solot, C.; Nicolson, S.C.; Spray, T.L.; Gaynor, J.W. (The Annals of thoracic surgery, 2010)
The purpose of this study was to assess deep hypothermic circulatory arrest (DHCA) as a modifier of neurodevelopmental (ND) outcomes in preschool children after cardiac surgery in infancy for repair of congenital heart defects (CHD). This is a planned analysis of infants enrolled in a prospective study of apolipoprotein E polymorphisms and ND outcome after cardiac surgery. The effect of DHCA was assessed in patients with single or biventricular CHD without aortic arch obstruction. Neurodevelopmental assessment at 4 years of age included cognition, language, attention, impulsivity, executive function, social competence, and visual-motor and fine-motor skills. Patient and procedural variables were evaluated in univariate and multivariate models. Neurodevelopmental testing was completed in 238 of 307 eligible patients (78%). Deep hypothermic circulatory arrest was used at the discretion of the surgeon at least once in 92 infants (38.6%) with a median cumulative duration of 36 minutes (range, 1 to 132 minutes). By univariate analysis, DHCA patients were more likely to have single-ventricle CHD (p = 0.013), lower socioeconomic status (p < 0.001), a higher incidence of preoperative ventilation (p < 0.001), and were younger and smaller at the first surgery (p < 0.001). By multivariate analysis, use of DHCA was not predictive of worse performance for any ND outcome. In this cohort of children undergoing repair of CHD in infancy, patients who underwent DHCA had risk factors associated with worse ND outcomes. Despite these, use of DHCA for repair of single-ventricle and biventricular CHD without aortic arch obstruction was not predictive of worse performance for any ND domain tested at 4 years of age. Copyright © 2010 The Society of Thoracic Surgeons. Published by Elsevier Inc. All rights reserved.
Keywords: article; child; cognition; comparative study; congenital heart malformation; deep hypothermic circulatory arrest; developmental disorder; female; follow up; human; incidence; infant; male; motor activity; newborn; physiology; postoperative period; preschool child; prognosis; prospective study; risk factor; time; United States

Functional outcomes after neonatal open cardiac surgery: Comparison of survivors of the Norwood staged procedure and the arterial switch operation - Alton, G.Y.; Rempel, G.R.; Robertson, C.M.T.; Newburn-Cook, C.V.; Norris, C.M. (Cardiology in the Young, 2010)
Background: Improvements in long-term survival of children undergoing the Norwood staged procedure and the arterial switch operation have resulted in the need to prepare these at-risk children for each stage of their developmental trajectory, including school readiness. This study describes and compares functional outcomes following the Norwood staged procedure and arterial switch operations.Methods This prospective inception cohort study comprised a sample of 73 children (71% boys) who had the Norwood staged procedure (n = 28) or the arterial switch operation (n = 45) at the age of 6 weeks or younger at the Stollery Childrens Hospital, Edmonton, Alberta, between 2002 and 2005. We excluded children who had chromosomal abnormalities or cerebral palsy. When children were 18-24 months of age, parents completed the Adaptive Behavioral Assessment System II. Standard scores for the domains are mean 100, standard deviation (15); skill area scaled scores, 10 (3). Students t-test with Bonferonni correction was used to compare groups.Results This population has greater than four times the number of children delayed on the General Adaptive Composite than the normative group. Functional outcomes were similar in the two groups other than those of home living (Norwood: 8.8 (2.8) compared with arterial switch: 11.2 (3.1), t = 3.389, p = 0.001) and self-care (Norwood: 5.9 (3.5) versus arterial switch: 8.1 (2.6), t = 3.140, p = 0.002).Conclusion These survivors are at increased risk for delayed functional abilities. Self-care, necessary for independence and confidence as children reach school age, was particularly low in the Norwood group. Reasons for low self-care abilities require further study. Copyright © Cambridge University Press 2010.
Keywords: adaptive behavior; arterial switch operation; article; blood vessel graft; child; clinical trial; cohort analysis; controlled clinical trial; controlled study; female; functional assessment; great vessels transposition; human; hypoplastic left heart syndrome; intermethod comparison; major clinical study; male; Norwood procedure; open heart surgery; outcome assessment; preschool child; prospective study; self care; survivor

Is cardiac diagnosis a predictor of neurodevelopmental outcome after cardiac surgery in infancy? - Gaynor, J.W.; Gerdes, M.; Nord, A.S.; Bernbaum, J.; Zackai, E.; Wernovsky, G.; Clancy, R.R.; Heagerty, P.J.; Solot, C.B.; McDonald-Mcginn, D.; Jarvik, G.P. (Journal of Thoracic and Cardiovascular Surgery, 2010)
Objectives: To determine whether a cardiac diagnosis is a predictor of neurodevelopmental outcomes after infant cardiac surgery. Methods: Infants with ventricular septal defect (VSD), tetralogy of Fallot (TOF), transposition of the great arteries (TGA), and hypoplastic left heart syndrome (HLHS) in a study of apolipoprotein E (APOE) polymorphisms, and neurodevelopmental outcome underwent neurodevelopmental and genetic evaluation at 4 years of age. The domains tested included cognition, language, speech, memory, executive function, visual-motor, fine motor, and reading and math skills. Results: Testing was completed in 178 patients with normal genetic evaluations: VSD (n = 26), TOF (n = 44), TGA (n = 41), and HLHS (n = 67). No differences were found in gestational age, ethnicity, APOE genotype, socioeconomic status, or maternal education among groups. Patient age at the first surgery was significantly lower for patients with TGA and HLHS compared with those with TOF and VSD. The postoperative length of stay was significantly longer for HLHS than all other groups and for TGA compared with TOF and VSD. HLHS correlated significantly with the use of deep hypothermic circulatory arrest and multiple operations. The mean scores for each domain were within normal limits for all groups. Compared with the other patients, those with HLHS had significantly lower scores for cognition, fine motor skills, executive function, and math skills. No significant differences were found among the TGA, TOF or VSD patients for any domain. Significant impairments in at least 1 domain were identified in 8% (2/25) of patients with VSD, 20% (8/41) with TOF, 17% (7/41) with TGA, and 18% (12/65) with HLHS. After correction for the demographic, preoperative, and operative variables, no significant differences were found among the groups for any domain. Conclusions: The mean scores for the neurodevelopmental outcomes domains tested were in the normal range for preschool children with no recognized genetic syndromes after surgery for VSD, TOF, TGA, and HLHS. In each diagnostic group, the number of children with impairments in at least 1 domain increased compared with the general population. Unadjusted neurodevelopmental outcomes for HLHS were lower for cognition, fine motor skills, executive function, and math skills compared with the other patients. After correction for the demographic, preoperative, and operative variables, no significant differences were found among the groups for any domain. The specific cardiac diagnosis determines a large portion of the variation in these covariates. Therefore, although HLHS did predict for poorer outcomes in some domains, it did not add predictive power to the other factors considered. © 2010 by The American Association for Thoracic Surgery.
Keywords: apolipoprotein E; article; child; cognition; controlled study; deep hypothermic circulatory arrest; diagnostic procedure; education; ethnicity; evaluation study; Fallot tetralogy; female; genetics; genotype; gestational age; great vessels transposition; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; infancy; infant; language; length of stay; major clinical study; male; memory; nerve cell differentiation; outcome assessment; preschool child; priority journal; protein polymorphism; reading; social status; speech; visuomotor coordination

Filament support spindle for an intravascular cavopulmonary assist device - Throckmorton, A.L.; Kapadia, J.Y.; Wittenschlaeger, T.M.; Medina, T.J.; Hoang, H.Q.; Bhavsar, S.S. (Artificial Organs, 2010)
We are developing an intravascular axial flow blood pump to support adolescent and adult Fontan patients. To protect the blood vessel, this pump has an outer cage with radially arranged filaments and a newly designed spindle at the pump outlet. The outlet spindle is included to limit the axial movement of the rotor and to house bearings that support the rotor. This study evaluates the impact of the outlet spindle on pump performance using computational fluid dynamics (CFD) and experimental testing of a prototype configuration. We measured the pressure-flow performance of the prototype with a protective cage using a blood analog fluid. The pump with the cage filaments and spindle generated 1 to 16 mm Hg of pressure rise for flow rates of 1 to 4 L/min at 4000 to 7000 rpm. The difference between the CFD predictions and experimental results was found to be approximately 9.8%. Scalar stress levels remained below 570 Pa with exposure times on the order of 1.5 s. These results are acceptable and support the continued development of this cavopulmonary assist device with an outlet spindle to reinforce the protective cage filament design. © 2010, the Authors. Artificial Organs © 2010, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: article; blood pump; cavopulmonary connection; computational fluid dynamics; flow rate; Fontan procedure; heart assist device; hydraulic conductivity; mechanical stress; performance measurement system; prediction; priority journal; pump design

Examination of the physical and psychosocial determinants of health behaviour in 4-5-year-old children with congenital cardiac disease - Casey, F.A.; Stewart, M.; McCusker, C.G.; Morrison, M.L.; Molloy, B.; Doherty, N.; Craig, B.G.; Sands, A.J.; Rooney, N.; Mulholland, H.C. (Cardiology in the Young, 2010)
Objectives: To assess the general health and activity levels of 4- and 5-year-old children after intervention for congenital cardiac disease. Methods: Health behaviour outcomes were assessed in 91 children who had surgery or catheter intervention for congenital cardiac disease. The children were classified into four groups according to severity. The main parameters of classification were the presence of residual symptoms, frequency of visits to general practitioner or the Accident and Emergency Department, and ability to participate in physical activity according to a calculated "activity score". Results: Children had very few residual symptoms after "corrective surgery". Those with complex congenital cardiac disease post-Fontan-type repair still had symptoms on average 18.2 days per month. Surprisingly, the complex group had fewer days "sick" from non-cardiac causes and had fewer visits to general practitioner or Accident and Emergency Departments. Regression analysis indicates that three variables had significant relevance to the general practitioner or Accident and Emergency visits: complex congenital cardiac disease, fewer visits; Townsend score - more deprivation - more visits; and maternal worry - higher maternal worry score - more visits. Regression analysis indicates that lower activity score is significantly related to complex cardiac disease and higher maternal worry score. Conclusions: The majority of this group of 4- and 5-year-old children had few residual symptoms and had good exercise tolerance. Maternal worry is a significant factor in influencing both activity levels and frequency of unscheduled health service demands - general practitioner or Accident and Emergency visits. Copyright © Cambridge University Press 2010.
Keywords: article; child; congenital heart disease; consultation; controlled study; disease classification; disease severity; exercise tolerance; Fontan procedure; general practitioner; health behavior; health care need; health status; heart catheterization; heart surgery; human; major clinical study; maternal behavior; medical care; parental behavior; physical activity; social psychology; symptom

European Resuscitation Council Guidelines for Resuscitation 2010 Section 6. Paediatric life support - Biarent, D.; Bingham, R.; Eich, C.; López-Herce, J.; Maconochie, I.; Rodríguez-Núñez, A.; Rajka, T.; Zideman, D. (Resuscitation, 2010)
Keywords: NCT00878644; NCT00880087; adenosine; epinephrine; alpha adrenergic receptor blocking agent; amiodarone; antipyretic agent; atropine; bicarbonate; calcium; dobutamine; dopamine; glucose; lidocaine; magnesium; naloxone; nitric oxide; noradrenalin; oxygen; procainamide; prostacyclin; terlipressin; vasopressin; absence of side effects; airway; airway obstruction; article; assisted ventilation; automated external defibrillator; blood glucose monitoring; bradycardia; breathing; calcium channel blocking agent overdose; calcium channel blocking agent overdose; capnometry; cardiac channelopathy; cardiopulmonary arrest; cardiopulmonary hemodynamics; child parent relation; child safety; childhood disease; childhood mortality; clinical trial; compression therapy; consciousness; continuous infusion; cricoid cartilage; decompression; defibrillation; defibrillator; disease course; drug dose titration; drug efficacy; drug half life; drug overdose; drug safety; drug substitution; electric potential; electrocardiography monitoring; emergency treatment; end tidal carbon dioxide tension; endotracheal intubation; endotracheal tube; extracorporeal circulation; family relation; fever; foreign body; heart arrest; heart arrhythmia; heart single ventricle; heart ventricle fibrillation; heart ventricle tachycardia; human; hyperkalemia; hypermagnesemia; hypocalcemia; hypomagnesemia; intensive care; international cooperation; laryngeal mask; lung ventilation perfusion ratio; medical device; metabolic acidosis; mouth; myocardial disease; oxygenation; patient safety; pediatric advanced life support; practice guideline; priority journal; prognosis; pulmonary hypertension; pulse oximetry; respiratory failure; resuscitation; single drug dose; supraventricular tachycardia; systemic vascular resistance; tachycardia; procedures

Pulmonary vascular resistance, collateral flow, and ventricular function in patients with a fontan circulation at rest and during dobutamine stress - Schmitt, B.; Steendijk, P.; Ovroutski, S.; Lunze, K.; Rahmanzadeh, P.; Maarouf, N.; Ewert, P.; Berger, F.; Kuehne, T. (Circulation: Cardiovascular Imaging, 2010)
Background-The role, interplay, and relative importance of the multifactorial hemodynamic and myocardial mechanisms causing dysfunction of the Fontan circulation remain incompletely understood. Methods and Results-Using an MRI catheterization technique, we performed a differential analysis of pulmonary vascular resistance and aortopulmonary collateral blood flow in conjunction with global ventricular pump function, myocontractility (end-systolic pressure-volume relation), and diastolic compliance (end-diastolic pressure-volume relation) in 10 patients with a Fontan circulation at rest and during dobutamine stress. Pulmonary and ventricular pressures were measured invasively and synchronized with velocity-encoded MRI-derived pulmonary and aortic blood flows and cine MRI-derived ventricular volumes. Pulmonary vascular resistance and end-systolic and end-diastolic pressure-volume relations were then determined. Aortopulmonary collateral flow was calculated as the difference between aortic and pulmonary flow. Compared to rest, dobutamine caused a small increase in mean pulmonary pressures (P<0.05). Collateral flow was significantly augmented (P<0.001) and contributed importantly to an increase in pulmonary flow (P<0.01). Pulmonary vascular resistance decreased significantly (P<0.01). Dobutamine did not increase stroke volumes significantly despite slightly enhanced contractility (end-systolic pressure-volume relation). Active early relaxation (τ) was inconspicuous, but the end-diastolic pressure-volume relation shifted upward, indicating reduced compliance. Conclusions-In patients with a Fontan circulation, aortopulmonary collateral flow contributes substantially to enhanced pulmonary flow during stress. Our data indicate that pulmonary vascular response to augmented cardiac output was adequate, but decreased diastolic compliance was identified as an important component of ventricular dysfunction. © 2010 American Heart Association, Inc.
Keywords: dobutamine; adolescent; adult; aortic flow; article; catheterization; circulation; clinical article; collateral circulation; controlled study; Fontan circulation; heart left ventricle enddiastolic pressure; heart left ventricle endsystolic volume; heart muscle contractility; heart stroke volume; heart ventricle function; heart ventricle pressure; human; lung blood flow; lung pressure; lung vascular resistance; nuclear magnetic resonance imaging; priority journal; physiological stress

Congenital heart surgery outcomes in down syndrome: Analysis of a national clinical database - Fudge Jr., J.C.; Li, S.; Jaggers, J.; O'Brien, S.M.; Peterson, E.D.; Jacobs, J.P.; Welke, K.F.; Jacobs, M.L.; Li, J.S.; Pasquali, S.K. (Pediatrics, 2010)
OBJECTIVE: We describe patient characteristics and postoperative morbidity and mortality rates for patients with Down syndrome undergoing congenital heart disease surgery. METHODS: This retrospective cohort study used the Society of Thoracic Surgeons Congenital Heart Surgery Database to compare patient characteristics and postoperative outcomes for patients (0-18 years) with or without Down syndrome who underwent surgery in 2000-2008. RESULTS: A total of 45 579 patients (4350 patients with Down syndrome and 41 229 without Down syndrome) were included (median age: 7 months [interquartile range [IQR]: 47 days to 4 years]; 56% male). Patients with Down syndrome were younger at surgery, with the exception of those undergoing tetralogy of Fallot repair or atrioventricular septal defect repair. Mortality rates for patients with or without Down syndrome did not differ significantly. Lengths of stay were prolonged for patients with Down syndrome undergoing atrial septal defect closure (median: 4 days [IQR: 3-5 days] vs 3 days [IQR: 2-4 days]; P < .0001), ventricular septal defect closure (median: 5 days [IQR: 4-8 days] vs 4 days [IQR: 3-6 days]; P < .0001), or tetralogy of Fallot repair (7 days [IQR: 5-10 days] vs 6 days [IQR: 5-9 days]; P < .001) and were associated with postoperative respiratory and infectious complications. Patients with Down syndrome undergoing ventricular septal defect closure had a higher rate of heart block requiring pacemaker placement (2.9% vs 0.8%; P < .0001). CONCLUSION: In this large, contemporary cohort, Down syndrome did not confer a significant mortality risk for the most common operations; however, postoperative morbidity remained common. Copyright © 2010 by the American Academy of Pediatrics.
Keywords: adolescent; adult; article; artificial heart pacemaker; cavopulmonary connection; child; clinical trial; cohort analysis; congenital heart disease; controlled study; data base; disease association; Down syndrome; endocarditis; Fallot tetralogy; female; Fontan procedure; heart atrium septum defect; heart block; heart rate; heart surgery; heart ventricle septum defect; human; infant; kidney failure; length of stay; major clinical study; male; mediastinitis; medical society; mitral valve repair; morbidity; multicenter study; neurologic disease; Norwood procedure; outcome assessment; postoperative complication; postoperative infection; postoperative period; preschool child; priority journal; pulmonary hypertension; respiratory tract infection; retrospective study; school child; seizure; sepsis; surgical mortality; systemic pulmonary shunt; treatment outcome; wound dehiscence

Balloon atrial septostomy guided by echocardiography in a neonatal intensive care unit - Lopes, L.M.; Kawano, C.; Cristóvão, S.A.B.; Nagamatsu, C.T.; Da Fonseca, L.; Furlanetto, B.H.S.; Furlanetto, G.; Da Silva, J.P.; Mangione, J.A. (Arquivos Brasileiros de Cardiologia, 2010)
Background: The bedside two-dimensional echocardiography (2-D ECHO) has been successfully used to guide the balloon atrial septostomy, speeding up the procedure and preventing the risks of transportation to the hemodynamics laboratory. Objective: To assess the results of the bedside balloon atrial septostomy in cyanotic neonates. Methods: Between January/1997 and July/2008, 102 atrioseptostomies by balloon catheter guided by echocardiography were carried out and saturation levels, defect diameter, oxygen saturation, clinical-laboratory response and complications related to the procedure were evaluated. Results: Of 102 cases of bedside Rashkind septostomy, 98 met the inclusion criteria, with 90 neonates in Group A (Rashkind procedure in the preoperative phase) and 8 in Group B (procedure at the postoperative phase). There was a predominance of the male sex (75%), mean age was 8.3 ± 9.3 days and the mean weight was 3,100 ± 1,100 g; the transposition of the great arteries was the most frequent congenital heart disease (n = 74). When comparing the levels of saturation pre and post-procedure (65.9 ± 19.5% and 86 ± 9.7%) and the diameter of the interatrial septal defect pre and post-procedure (2.3 ± 1.0 mm and 5.5 ± 1.3 mm) there was a statistically significant difference (p < 0.001). When comparing the levels of saturation and the diameter of the interatrial septal defect between the group of survivors vs non-survivor, there was no statistically significant difference (p < 0.05). Conclusion: The balloon atrial septostomy guided by the echocardiography reduces the risks by allowing the effective palliative procedure to be carried out promptly in cyanotic neonates, in addition to presenting lower hospital costs.
Keywords: article; balloon atrial septostomy; balloon catheter; fatality; female; great vessels transposition; atrial fibrillation; interatrial septum; heart atrium septum defect; heart surgery; heart tamponade; heart ventricle tachycardia; human; hypoplastic left heart syndrome; major clinical study; male; newborn; newborn intensive care; outcome assessment; oxygen saturation; palliative therapy; risk reduction; surgical technique; two dimensional echocardiography

Differential changes in TGF-β/BMP signaling pathway in the right ventricular myocardium of newborns with hypoplastic left heart syndrome - Ricci, M.; Mohapatra, B.; Urbiztondo, A.; Birusingh, R.J.; Morgado, M.; Rodriguez, M.M.; Lincoln, J.; Vatta, M. (Journal of Cardiac Failure, 2010)
Background: Hypoplastic left heart syndrome (HLHS) is characterized by underdevelopment of the left ventricle (LV) and increased biomechanical stress on the right ventricle (RV) from single ventricle physiology. Despite the clinical significance, the signaling pathways active during RV remodeling and disease progression are not known. To address this, we examined differential changes in expression of genes associated with transforming growth factor-β (TGF-β)/bone morphogenetic protein (BMP) signaling in RV tissue isolated from HLHS patients relative to RV and LV tissue from control subjects. Methods and Results: Quantitative real-time polymerase chain reaction was used to detect changes in expression of 84 genes involved in TGF-β/BMP-mediated cardiac development, cell growth, and differentiation in RV tissue collected from 6 neonates with HLHS undergoing stage 1 Norwood procedure (age, 1-7 days; mean, 4 days) and RV and LV tissue obtained from 5 infants with noncardiac pathology (age range, 1-135 days: mean, 85 days) that served as controls. Analysis of gene expression profiles between control-LV and control-RV revealed significant depression of TGF-β/BMP signaling in RV compared with LV. Of the 84 genes analyzed, 38 were differentially expressed between HLHS-RV and control-RV, whereas only 22 compared with control-LV. Significant changes were observed in: tissue remodeling genes including Activin receptor type IIA (ACVR2A) (+2.13) and Activin receptor-like kinase 1 (ACVRL1) (+2.22); and cell survival, growth, and differentiation genes including CDC25A (+2.18), p21 (-3.64), p15 (+2.15), BMP5 (+4.58), BMP3 (+2.16), GDF3 (+8.59), NODAL (+2.32), and BMP binding endothelial regulator (BMPER) (+4.58). The most significant changes common to HLHS-RV versus control-RV and control-LV sample groups is observed for Anti müllerian hormone receptor 2 (AMHR2) (+18.79 control-RV, +3.38 control-LV), and the BMP antagonist Inhibin alpha (INHA) (+11.47 control-RV, +5.73 control-LV). Conclusions: Although this descriptive study does not allow cause-effect inferences, our results suggest changes in cardiac development pathways and upregulation of genes associated with cell growth and differentiation in the neonatal RV of children with HLHS. These molecular profiles are more closely related to those observed in the normal LV rather than normal RV at similar maturational age. This work provides the basis for future mechanistic studies to elucidate the molecular mechanisms regulating RV remodeling in HLHS. © 2010 Elsevier Inc. All rights reserved.
Keywords: activin receptor 2; activin receptor like kinase 1; bone morphogenetic protein; bone morphogenetic protein 5; cyclin dependent kinase; growth differentiation factor 3; osteogenin; transforming growth factor beta; article; cell growth; cell survival; clinical article; controlled study; female; gene expression; genetic variability; gestational age; heart development; heart left ventricle; cardiac muscle; heart right ventricle; human; hypoplastic left heart syndrome; male; newborn; priority journal; real time polymerase chain reaction; signal transduction

Computational hemodynamic analysis in congenital heart disease: simulation of the Norwood procedure. - Qian, Y.; Liu, J.L.; Itatani, K.; Miyaji, K.; Umezu, M. (Annals of biomedical engineering, 2010)
Hypoplastic left heart syndrome (HLHS) is a congenital heart disease which should be treated at neonate. Even now, its operation is one of the greatest challenges. However, currently there are no quantitative standards to evaluate and predict the outcome of the therapy. In this study, computational fluid dynamics (CFD) was used to estimate the performance of first stage HLHS surgery, the Norwood operation. An image data transfer system was developed to convert clinical images into three-dimensional geometry. To confirm software applicability, a validation process was carried out to eliminate any influence of numerical procedures. The velocities derived from echocardiography measurements were used as boundary conditions, and pressure waves measured by a cardiac catheter simultaneous with an electrocardiogram (ECG) were employed to validate the results of CFD simulation. Calculated results were congruent with the in vivo measurement results. The blood flow circulations were successfully simulated and the distribution of blood flow in each vessel was estimated. Time-varying energy losses (EL), local pressure and wall shear stress (WSS) were analyzed to estimate clinical treatment. The results indicated that pulsatile simulation is essential in quantitative evaluation. Computational hemodynamics may be applied in the surgical optimization for the treatment of HLHS.
Keywords: article; cardiovascular surgery; software; computer simulation; congenital heart malformation; female; heart disease; hemodynamics; human; hypoplastic left heart syndrome; mechanical stress; newborn; physiology

8p23.1 duplication syndrome differentiated from copy number variation of the defensin cluster at prenatal diagnosis in four new families - Barber, J.C.; Bunyan, D.; Curtis, M.; Robinson, D.; Morlot, S.; Dermitzel, A.; Liehr, T.; Alves, C.; Trindade, J.; Paramos, A.I.; Cooper, C.; Ocraft, K.; et al. (Molecular Cytogenetics, 2010)
Background: The 8p23.1 duplication syndrome and copy number variation of the 8p23.1 defensin gene cluster are cytogenetically indistinguishable but distinct at the molecular level. To our knowledge, the 8p23.1 duplication syndrome has been described at prenatal diagnosis only once and we report our experience with four further apparent duplications ascertained at prenatal diagnosis. Methods. Additional material at band 8p23.1 was detected using conventional G-banded cytogenetics in each case. Multiplex Ligation-dependent Probe Amplification (MLPA) or Fluorescence In Situ Hybridisation (FISH) were used depending on whether only DNA (Cases 1 and 4) or cytogenetic preparations (Cases 2 and 3) were available from the laboratory of origin. The extent of the duplication in Case 1 was retrospectively determined using array Comparative Genomic Hybridisation (array CGH). Results. Three cases of 8p23.1 duplication syndrome were found (Cases 1 to 3). Two were de novo and continued to term and the third, a paternally transmitted duplication, was terminated because of a previous child with psychomotor delay and 8p23.1 duplication syndrome. Case 1 was ascertained with a hypoplastic left heart but the ventricular septal and interventricular defects, in Cases 2 and 3 respectively, were found after ascertainment for advanced maternal age. By contrast, case 4 was a maternally transmitted copy number variation of the defensin cluster with normal outcome. Conclusions. Our data underline the need to differentiate 8p23.1 duplications from copy number variation of the defensin cluster using FISH, MLPA or array CGH. Cardiac defects were ascertained by ultrasound in only one of the three duplication 8p23.1 pregnancies but were visible in two of the three at 21 to 22 weeks gestation. Our results provide further evidence that both deletion and duplication of the GATA4 transcription factor can give rise to a variety of conotruncal heart defects with variable penetrance and expressivity. © 2010 Barber et al; licensee BioMed Central Ltd.
Keywords: defensin; transcription factor GATA 4; 8p23.1 duplication syndrome; adult; amniocentesis; article; chromosome 8p; chromosome analysis; chromosome band; chromosome duplication; chromosome number; chromosome variant; comparative genomic hybridization; copy number variation; female; fluorescence in situ hybridization; gene cluster; gestational age; heart catheterization; heart ventricle septum defect; human; hypoplastic left heart syndrome; maternal age; pregnancy outcome; prenatal diagnosis; priority journal; psychomotor disorder

Molecular evidence of perinatal transmission of Bartonella vinsonii subsp. berkhoffii and Bartonella henselae to a child - Breitschwerdt, E.B.; Maggi, R.G.; Farmer, P.; Mascarelli, P.E. (Journal of Clinical Microbiology, 2010)
Bartonella vinsonii subsp. berkhoffii, Bartonella henselae, or DNA of both organisms was amplified and sequenced from blood, enrichment blood cultures, or autopsy tissues from four family members. Historical and microbiological results support perinatal transmission of Bartonella species in this family. It is of clinical relevance that Bartonella spp. may adversely influence human reproductive performance. Copyright © 2010, American Society for Microbiology. All Rights Reserved.
Keywords: azithromycin; ciprofloxacin; DNA; doxycycline; fluconazole; nitazoxanide; nystatin; adult; amnesia; arthralgia; article; autopsy; balance disorder; Bartonella; Bartonella berkhoffii; Bartonella henselae; Bartonella vinsonii; bladder dysfunction; Blastocystis hominis; blastocystosis; blood culture; candidiasis; case report; cesarean section; child; chlamydial pneumonia; cognitive defect; confusion; dyspnea; ear infection; fatigue; female; female infertility; in vitro fertilization; food allergy; gene amplification; gene sequence; genital pain; headache; human; human tissue; hypoplastic left heart syndrome; insomnia; interstitial cystitis; irritability; irritable colon; male; myalgia; Mycoplasma pneumonia; night sweat; nucleotide sequence; perinatal infection; priority journal; pruritus; restlessness; school child; sinusitis; tachycardia; verruca vulgaris; vertical transmission

Dual-platform proteomics study of plasma biomarkers in pediatric patients undergoing cardiopulmonary bypass - Umstead, T.M.; Lu, C.-J.K.; Freeman, W.M.; Myers, J.L.; Clark, J.B.; Thomas, N.J.; Chinchilli, V.M.; Vrana, K.E.; Ündar, A.; Phelps, D.S. (Pediatric Research, 2010)
Plasma samples from pediatric cardiac patients undergoing cardiopulmonary bypass (CPB) procedures were used to identify and characterize patterns of changes in potential biomarkers related to tissue damage and inflammation. These included proteins associated with systemic inflammatory response syndrome. Potential biomarkers were identified using a dual-platform proteomics approach requiring ∼150 μL of plasma, which included two-dimensional difference gel electrophoresis (2D-DIGE) and a multiplexed immunoassay. Methods used in the dual approach measured levels of 129 proteins in plasma from pediatric CPB patients. Of these, 70 proteins changed significantly (p < 0.05) between time points, and 36 of these retained significance after the highly stringent Bonferroni correction [p < 0.001 for 2D-DIGE and p < 0.00056 for multianalyte profile (MAP) assays]. Many of the changing proteins were associated with tissue damage, inflammation, and oxidative stress. This study uses a novel approach that combines two discovery proteomics techniques to identify a pattern of potential biomarkers changing after CPB. This approach required only 150 μL of plasma per time point and provided quantitative information on 129 proteins. The changes in levels of expression of these proteins may provide insight into the understanding, treatment, and prevention of systemic inflammation, thereby helping to improve the outcomes of pediatric CPB patients. © 2010 International Pediatric Research Foundation, Inc.
Keywords: albumin; alpha 1 antichymotrypsin; alpha 1 antitrypsin; alpha 2 macroglobulin; alpha globulin; angiotensinogen; apolipoprotein A1; apolipoprotein A2; aryldialkylphosphatase; biological marker; blood clotting factor 13b; complement component C3; complement component C6; complement factor I; fetuin A; fibrinogen; haptoglobin; hemopexin; immunoglobulin A; immunoglobulin G; immunoglobulin M; kininogen; orosomucoid; transthyretin; serum amyloid P; sex hormone binding globulin; tetranectin; thrombin; transferrin; article; blood sampling; cardiopulmonary bypass; child; clinical article; controlled study; endocardial cushion defect; Fallot tetralogy; female; Fontan procedure; heart atrium septum defect; heart ventricle septum defect; human; immunoassay; infant; inflammation; male; matrix assisted laser desorption ionization time of flight mass spectrometry; oxidative stress; preschool child; priority journal; protein analysis; protein expression; proteomics; quantitative analysis; systemic inflammatory response syndrome; tissue injury; two dimensional gel electrophoresis

Thoracoscopic repair in congenital diaphragmatic hernia: patching is safe and reduces the recurrence rate - Keijzer, R.; van de Ven, C.; Vlot, J.; Sloots, C.; Madern, G.; Tibboel, D.; Bax, K. (Journal of Pediatric Surgery, 2010)
Purpose: Congenital diaphragmatic hernia (CDH) has traditionally been repaired via a laparotomy. More and more reports on thoracoscopic repair are being published. The aim of this study was to evaluate our series of thoracoscopic CDH repair and compare this group to an open repair group treated during the same period in the same institute. Patients and Methods: Between June 2006 and December 2008, 49 children with posterolateral CDH were admitted, of whom 23 (47%) were operated thoracoscopically and 23 (47%) using an open repair, depending on the discretion of the attending surgeon and the clinical condition of the patient. Three patients (6%) with CDH were not treated because of associated anomalies (twice Cornelia de Lange syndrome and once hypoplastic left heart syndrome). Six thoracoscopic operations (26%) were converted to open surgery. Nine defects (39%) were closed thoracoscopically without a patch. In 8 (35%) patients, a patch was used. We used a patch in 20 open procedures (87%). Results: Three (33%) of the 9 thoracoscopic repairs without patch and 1 (12%) of the 8 with a patch developed a recurrence. All these recurrences were repaired thoracoscopically. The 3 recurrences from the thoracoscopic primary repair were repaired using a patch. In the open group, 3 patients (13%) developed a recurrence, of whom 2 were repaired thoracoscopically. Mean operative time was significantly longer in the thoracoscopic patch repair group (158 minutes), when compared to the open repair group (125 minutes). Conclusion: As in open repair, it seems wise to use large patches liberally, not only to reconstruct the dome of the diaphragm but also to avoid undue tension on the repair and prevent recurrences. The thoracoscopic approach is also considered feasible in case of a recurrence from either a thoracoscopic or open repair. © 2010 Elsevier Inc. All rights reserved.
Keywords: article; brain infarction; child; chylothorax; clinical article; congenital diaphragm hernia; controlled study; de Lange syndrome; female; hematothorax; human; hypoplastic left heart syndrome; length of stay; male; operation duration; priority journal; pulmonary hypertension; recurrence risk; risk reduction; safety; surgical mortality; suture; thoracoscopic patch repair; thoracoscopy

Intravascular ultrasound catheter for transesophageal echocardiography in congenital heart surgery - A case report - Kim, H.-J.; Kim, J.-Y.; Baek, S.-H.; Kim, H.-K. (Korean Journal of Anesthesiology, 2010)
Transesophageal echocardiography (TEE) has an important role during congenital heart surgery. TEE in small infants is associated with complications, including an inability to pass the TEE probe, esophageal trauma, airway compression, aortic compression, and interference with ventilation. Recently, a monoplane intravascular ultrasound catheter (IVUC) has been developed for intracardiac echocardiography. The efficacy of IVUC for transesophageal use has been shown in numerous animal studies and several human studies, but there have been few reports involving small infants using an IVUC probe. We examined 15 pediatric patients undergoing congenital cardiac surgery using an 8-Fr AcuNav IVUC probe. We checked the cardiac anatomy, cardiac function pre-operatively and de-aeration before weaning from CPB; the surgical repairs were evaluated post-operatively. Although the IVUC probe has limitations associated with the monoplane, we found the IVUC probe to be useful in small infants and safer than the TEE. Copyright © Korean Society of Anesthesiologists, 2010.
Keywords: fentanyl; midazolam; sevoflurane; anesthesia induction; anesthesiological procedure; aortic arch interruption; aortic coarctation; arterial pressure; article; artificial ventilation; blood pressure monitoring; capnometry; central venous pressure; clinical article; echocardiography; electrocardiography; Fallot tetralogy; great vessels transposition; heart atrium septum defect; heart function; heart right ventricle outflow tract; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; infant; intravascular catheter; intravascular ultrasound; invasive procedure; lung artery pressure; lung blood flow; maintenance therapy; mechanical probe; newborn; Norwood procedure; oximetry; patient monitoring; patient safety; pediatric surgery; postoperative period; preoperative evaluation; pressure gradient; pulmonary artery; pulmonary valve; pulmonary valve disease; pulse oximetry; temperature measurement; transesophageal echocardiography; AcuNav

Multi-institutional studies: Lessons learned from the pediatric heart network single ventricle reconstruction trial - Ohye, R.G. (Seminars in Thoracic and Cardiovascular Surgery: Pediatric Cardiac Surgery Annual, 2010)
This session of the Congenital Post-Graduate Course 89th Annual Meeting of the American Association for Thoracic Surgery focused on clinical research in pediatric cardiac surgery. This particular lecture concentrated on the management of clinical trials from the viewpoint of a multi-institutional trial, utilizing my experiences as the Study Co-Chair of the National Heart Lung Blood Institute (NHLBI)-funded, Pediatric Heart Network Single Ventricle Reconstruction (SVR) Trial. Preparing for the role as a Primary Investigator through coursework and reading is an important prerequisite. Study design requires thoughtful crafting of the primary question, secondary question, and subanalyses. Often the challenge is not what to include, but what to exclude, to develop a practical database. Getting your co-investigators invested in the trial is crucial, as subject enrollment is time-consuming and will determine the success or failure of your trial. © 2010 Elsevier Inc.
Keywords: article; childhood disease; clinical protocol; clinical research; clinical study; clinical trial; data base; health care management; health center; heart single ventricle; heart ventricle remodeling; human; investment; pediatric surgery; personal experience; process design; professional competence; reading; study design

Mortality After Total Cavopulmonary Connection in Children With the Down Syndrome - Gupta-Malhotra, M.; Larson, V.E.V.; Rosengart, R.M.; Guo, H.; Moller, J.H. (American Journal of Cardiology, 2010)
A total cavopulmonary connection (Fontan surgery) is rarely performed in a child with trisomy 21 (Down syndrome) for a univentricular heart, and the outcomes after surgery are not well defined, but the incidence of mortality has been reported to be higher. To determine the mortality rate and contributing factors after Fontan surgery in children with Down syndrome, mortality data after Fontan surgery from the Pediatric Cardiac Care Consortium Registry were evaluated. Among Fontan procedures (n = 2,853), all patients with Down syndrome (n = 17) were selected, of whom 13 had hemodynamic data available. Thirteen children without chromosomal aberrations were then selected as a control group, matched 1 to 1 for gender, age, weight, lesion, and type of Fontan procedure. The following variables were evaluated: pulmonary artery pressure and vascular resistance, weight, hemoglobin, degree of atrioventricular regurgitation, previous Glenn operation, fenestration, and length of stay in the hospital. In children with Down syndrome, mortality after the Glenn operation was 28%. Mortality after the Fontan operation was increased significantly (p = 0.001) in children with Down syndrome (35%) compared with those without Down syndrome (10%). Between patients with Down syndrome and controls, there were no significant differences in the perioperative parameters evaluated. Almost all mortality was in the early postoperative period in children with Down syndrome. The relative risk ratio of mortality was 2.5 (95% confidence interval 0.63 to 10). In conclusion, Down syndrome was found to be an independent parameter associated with a significantly higher risk for mortality in the early postoperative period after Fontan surgery. © 2010 Elsevier Inc. All rights reserved.
Keywords: hemoglobin; article; body weight; cavopulmonary connection; child; chromosome aberration; clinical article; controlled study; Down syndrome; female; Fontan procedure; Glenn shunt; hemodynamics; human; incidence; length of stay; lung artery pressure; male; perioperative period; postoperative period; preschool child; priority journal; risk factor; school child; surgical mortality; tricuspid valve regurgitation; vascular resistance

Attitudes and practices of cardiologists and surgeons who manage HLHS - Prsa, M.; Holly, C.D.; Carnevale, F.A.; Justino, H.; Rohlicek, C.V. (Pediatrics, 2010)
OBJECTIVE: We conducted a survey to determine which management options pediatric cardiologists and cardiac surgeons in North America discuss and recommend when counseling parents after the diagnosis of hypoplastic left heart syndrome (HLHS). METHODS: Pediatric cardiologists and cardiac surgeons across North America were asked to complete an anonymous, Internet-based survey about their attitudes and practices regarding the management of HLHS. RESULTS: We contacted 1621 pediatric cardiologists and surgeons, of whom 749 (46%) completed the survey. When counseling parents of newborns with HLHS, 99.7% of respondents discussed staged palliative surgery, 67% discussed cardiac transplantation, and 62.2% discussed compassionate care without surgery. Only a minority (14.9%) discussed all of those options. Staged palliative surgery was recommended over cardiac transplantation or compassionate care without surgery by 76.2% of respondents. When counseling parents after prenatal diagnosis of HLHS, 98.8% of respondents discussed continuation of pregnancy with staged palliative surgery after birth, 53.5% discussed continuation of pregnancy with cardiac transplantation after birth, 56.9% discussed continuation of pregnancy with compassionate care after birth, and 74.3% discussed termination of pregnancy. Only 36.5% discussed all of those options. Continuation of pregnancy with staged palliative surgery after birth was recommended over the other options by 56% of respondents. CONCLUSIONS: Virtually all North American pediatric cardiologists and cardiac surgeons surveyed discuss a surgical intervention when counseling parents about the care of their child or fetus with HLHS. However, only a minority discuss all options. Most physicians recommend staged palliative surgery for management of HLHS. Copyright © 2010 by the American Academy of Pediatrics.
Keywords: article; birth; cardiologist; compassionate; emotion; health survey; heart transplantation; human; hypoplastic left heart syndrome; Internet; medical practice; medical specialist; North America; palliative therapy; parent counseling; pediatrics; physician attitude; pregnancy; pregnancy termination; priority journal

The value of transesophageal echocardiography to detect coronary artery stenosis in children - Al-Qbandi, M.A.; Smallhorn, J. (Kuwait Medical Journal, 2010)
Objective: To assess the utility of transesophageal echocardiography (TEE) in the detection of proximal coronary artery (CA) stenoses in children undergoing cardiac surgery Design: Longitudinal cohort study conducted between January 2000 and April 2008 Setting: Chest Diseases Hospital, Kuwait and the University of Toronto, Canada. Subjects: Fifteen patients of either sex, aged between three days to 17 years (median = 8 years, 8 female) identi.ed as having proximal CA stenosis by TEE Interventions: Pre and postoperative TEE done in all patients where CA surgery was performed Main Outcome Measures: Patients with proximal CA Doppler and color .ow patterns suggestive of proximal CA stenosis after cardiac surgery were identi.ed. The clinical, echocardiographic, angiographic and autopsy data were reviewed. Results: We identi.ed with TEE proximal CA stenoses after Ross-Konno (5/15), arterial switch repair (2/15), repair of supravalvar AS (2/15), reimplantation of ALCA (2/15), complex AV and sub-AV stenosis (1/15), isolated supravalvar PS (1/15), post-Norwood stage I (1/15) and redo of RV to PA conduit (1/15). RCA stenoses were identi.ed in nine and LCA stenoses in six cases. Six cases had anomalous origin of CA diagnosed preoperatively. Three Doppler .ow patterns were identi.ed. Wall motion abnormalities were seen in all cases. The result of TEE of CA's altered immediate surgical management in eight patients. Conclusion: TEE imaging and Doppler interrogation of the proximal CAs reliably detects stenoses and may provide important information leading to surgical revision of the CA anastomoses. We suggest routine perioperative TEE assessment of proximal CA anastomoses following surgical reimplantation.
Keywords: adolescent; angiocardiography; aortic regurgitation; aortic valve stenosis; artery reconstruction; artery wall; article; autopsy; child; childhood disease; clinical article; cohort analysis; color Doppler flowmetry; congestive cardiomyopathy; coronary artery anomaly; coronary artery obstruction; coronary artery surgery; coronary stent; diagnostic value; Doppler echocardiography; endocardial fibroelastosis; female; great vessels transposition; heart left ventricle outflow tract obstruction; hospitalized child; human; hypoplastic left heart syndrome; infant; left coronary artery; longitudinal study; male; preschool child; right coronary artery; school child; transesophageal echocardiography; Williams Beuren syndrome

A New Multiparameter Approach to Computational Simulation for Fontan Assessment and Redesign - Marsden, A.L.; Reddy, V.M.; Shadden, S.C.; Chan, F.P.; Taylor, C.A.; Feinstein, J.A. (Congenital Heart Disease, 2010)
Introduction: Despite an abundance of prior Fontan simulation articles, there have been relatively few clinical advances that are a direct result of computational methods. We address a few key limitations of previous Fontan simulations as a step towards increasing clinical relevance. Previous simulations have been limited in scope because they have primarily focused on a single energy loss parameter. We present a multi-parameter approach to Fontan modeling that establishes a platform for clinical decision making and comprehensive evaluation of proposed interventions. Methods: Time-dependent, 3-D blood flow simulations were performed on six patient-specific Fontan models. Key modeling advances include detailed pulmonary anatomy, catheterization-derived pressures, and MRI-derived flow with respiration. The following performance parameters were used to rank patients at rest and simulated exercise from best to worst performing: energy efficiency, inferior and superior vena cava (IVC, SVC) pressures, wall shear stress, and IVC flow distribution. Results: Simulated pressures were well matched to catheterization data, but low Fontan pressure did not correlate with high efficiency. Efficiency varied from 74% to 96% at rest, and from 63% to 91% with exercise. Distribution of IVC flow ranged from 88%/12% (LPA/RPA) to 53%/47%. A " transcatheter" virtual intervention demonstrates the utility of computation in evaluating interventional strategies, and is shown to result in increased energy efficiency. Conclusions: A multiparameter approach demonstrates that each parameter results in a different ranking of Fontan performance. Ranking patients using energy efficiency does not correlate with the ranking using other parameters of presumed clinical importance. As such, current simulation methods that evaluate energy dissipation alone are not sufficient for a comprehensive evaluation of new Fontan designs. © 2010 Copyright the Authors. Journal Compilation © 2010 Wiley Periodicals, Inc.
Keywords: adolescent; adult; article; audiovisual equipment; blood flow; breathing; child; clinical article; computational fluid dynamics; contrast enhancement; energy; exercise; female; Fontan procedure; heart catheterization; hemodynamics; human; inferior cava vein; male; multidetector computed tomography; nuclear magnetic resonance imaging; parameters; performance; preschool child; priority journal; rest; shear stress; simulation; superior cava vein; venous pressure; Sensation 16; Signa Twin Speed

Optimization of inflow waveform phase-difference for minimized total cavopulmonary power loss - Dur, O.; DeGroff, C.G.; Keller, B.B.; Pekkan, K. (Journal of Biomechanical Engineering, 2010)
The Fontan operation is a palliative surgical procedure performed on children, born with congenital heart defects that have yielded only a single functioning ventricle. The total cavo-pulmonary connection (TCPC) is a common variant of the Fontan procedure, where the superior vena cava (SVC) and inferior vena cava (IVC) are routed directly into the pulmonary arteries (PA). Due to the limited pumping energy available, optimized hemodynamics, in turn, minimized power loss, inside the TCPC pathway is required for the best optimal surgical outcomes. To complement ongoing efforts to optimize the anatomical geometric design of the surgical Fontan templates, here, we focused on the characterization of power loss changes due to the temporal variations in between SVC and IVC flow waveforms. An experimentally validated pulsatile computational fluid dynamics solver is used to quantify the effect of phase-shift between SVC and IVC inflow waveforms and amplitudes on internal energy dissipation. The unsteady hemodynamics of two standard idealized TCPC geometries are presented, incorporating patient-specific real-time PC-MRI flow waveforms of "functional" Fontan patients. The effects of respiration and pulsatility on the internal energy dissipation of the TCPC pathway are analyzed. Optimization of phase-shift between caval flows is shown to lead to lower energy dissipation up to 30% in these idealized models. For physiological patient-specific caval waveforms, the power loss is reduced significantly (up to 11%) by the optimization of all three major harmonics at the same mean pathway flow (3 L/min). Thus, the hemodynamic efficiency of single ventricle circuits is influenced strongly by the caval flow waveform quality, which is regulated through respiratory dependent physiological pathways. The proposed patient-specific waveform optimization protocol may potentially inspire new therapeutic applications to aid postoperative hemodynamics and improve the well being of the Fontan patients. Copyright © 2010 by ASME.
Keywords: article; breathing; cavopulmonary connection; computational fluid dynamics; coronary artery blood flow; Fontan procedure; inferior cava vein; nuclear magnetic resonance imaging; process optimization; real time polymerase chain reaction; superior cava vein; surgical technique; waveform

Laboratory measures of exercise capacity and ventricular characteristics and function are weakly associated with functional health status after fontan procedure - McCrindle, B.W.; Zak, V.; Sleeper, L.A.; Paridon, S.M.; Colan, S.D.; Geva, T.; Mahony, L.; Li, J.S.; Breitbart, R.E.; Margossian, R.; Williams, R.V.; Gersony, W.M.; et al. (Circulation, 2010)
Background: Patients after the Fontan procedure are at risk for suboptimal functional health status, and associations with laboratory measures are important for planning interventions and outcome measures for clinical trials. Methods and Results: Parents completed the generic Child Health Questionnaire for 511 Fontan Cross-Sectional Study patients 6 to 18 years of age (61% male). Associations of Child Health Questionnaire Physical and Psychosocial Functioning Summary Scores (FSS) with standardized measurements from prospective exercise testing, echocardiography, magnetic resonance imaging, and measurement of brain natriuretic peptide were determined by regression analyses. For exercise variables for maximal effort patients only, the final model showed that higher Physical FSS was associated only with higher maximum work rate, accounting for 9% of variation in Physical FSS. For echocardiography, lower Tei index (particularly for patients with extracardiac lateral tunnel connections), lower indexed end-systolic volume, and the absence of atrioventricular valve regurgitation for patients having Fontan procedure at age <2 years were associated with higher Physical FSS, accounting for 14% of variation in Physical FSS. For magnetic resonance imaging, ratio of lower mass to end-diastolic volume and midquartiles of indexed end-systolic volume (nonlinear) were associated with higher Physical FSS, accounting for 11% of variation. Lower brain natriuretic peptide was significantly but weakly associated with higher Physical FSS (1% of variation). Significant associations for Psychosocial FSS with laboratory measures were fewer and weaker than for Physical FSS. Conclusions: In relatively healthy Fontan patients, laboratory measures account for a small proportion of the variation in functional health status and therefore may not be optimal surrogate end points for trials of therapeutic interventions. © 2010 American Heart Association. All rights reserved.
Keywords: brain natriuretic peptide; adolescent; adult; article; cardiopulmonary exercise test; child; controlled study; echocardiography; exercise; female; Fontan procedure; health status; heart hemodynamics; heart ventricle function; human; male; nuclear magnetic resonance imaging; preschool child; priority journal; school child; scoring system; structured questionnaire; tricuspid valve regurgitation

Maternal obesity and morbid obesity: The risk for birth defects in the offspring - Blomberg, M.I.; Källén, B. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2010)
BACKGROUND: The objective of this study was to assess, in a large data set from Swedish Medical Health Registries, whether maternal obesity and maternal morbid obesity were associated with an increased risk for various structural birth defects. METHODS: The study population consisted of 1,049,582 infants born in Sweden from January 1, 1995, through December 31, 2007, with known maternal weight and height data. Women were grouped in six categories of body mass index (BMI) according to World Health Organization classification. Infants with congenital birth defects were identified from three sources: the Swedish Medical Birth Registry, the Register of Birth Defects, and the National Patient Register. Maternal age, parity, smoking, and year of birth were thought to be potential confounders and were included as covariates in the adjusted odds ratio analyses. RESULTS: Ten percent of the study population was obese. Morbid obesity (BMI ≥ 40) occurred in 0.7%. The prevalence of congenital malformations was 4.7%, and the prevalence of relatively severe malformations was 3.2%. Maternal prepregnancy morbid obesity was associated with neural tube defects OR 4.08 (95% CI 1.87-7.75), cardiac defects OR 1.49 (95% CI 1.24-1.80), and orofacial clefts OR 1.90 (95% CI 1.27-2.86). Maternal obesity (BMI ≥ 30) significantly increased the risk of hydrocephaly, anal atresia, hypospadias, cystic kidney, pes equinovarus, omphalocele, and diaphragmatic hernia. CONCLUSION: The risk for a morbidly obese pregnant woman to have an infant with a congenital birth defect is small, but for society the association is important in the light of the ongoing obesity epidemic. © 2009 Wiley-Liss, Inc.
Keywords: abdominal wall defect; anus atresia; article; congenital malformation; body height; body mass; body weight; choana atresia; cigarette smoking; cleft face; congenital heart malformation; controlled study; craniofacial synostosis; diaphragm hernia; disease severity; ear malformation; esophagus atresia; Fallot tetralogy; female; great vessels transposition; high risk pregnancy; human; hydrocephalus; hypoplastic left heart syndrome; hypospadias; infant; intestine atresia; kidney agenesis; kidney polycystic disease; limb reduction defect; major clinical study; maternal age; maternal disease; maternal obesity; maternal smoking; microcephaly; microphthalmia; morbid obesity; mouth malformation; neural tube defect; obesity; omphalocele; orofacial cleft; parity; clubfoot; priority journal; progeny; risk factor; Sweden

One center experience in pulmonary artery stenting without long vascular sheath - Moszura, T.; Michalak, K.W.; Dryzek, P.; Moll, J.A.; Moll, J.; Sysa, A. (Cardiology Journal, 2010)
Background: Pulmonary artery stenting without a long vascular sheath has a special significance, particularly for children with low body weight. Using only a short sheath often permits the implantion of a stent of the correct size; moreover, it improves access to peripherally located stenoses. The aim of this paper is to present the results of a balloon expandable stent implantation into pulmonary arteries without using a long vascular sheath. Methods: The subjects were divided into two groups. The first group (28 patients, mean age 3.2 years) comprised patients with a single-ventricle heart after bi-directional Glenn procedure (Fontan procedure). The second group (22 patients, mean age 8.3 years) consisted of patients with a two-ventricle heart. Patients were retrospectively analyzed with regard to stenosis size widening and change in trans-stenotic pressure gradient after stenting. Results: In our data, no statistically significant differences between the two groups in terms of the number of complications and incorrect stent position following implantation were noted (3% and 4%). Good treatment results, with a decrease in trans-stenotic pressure gradient in the first group of 3.2 mm and in the second group of 13.4 mm of mercury, and a widening of the stenosis, were obtained in most cases in both groups (97% and 96%). The average change of the vessel's diameter was in the first group 4.2 mm and in the second 5.4 mm. Conclusions: The obtained results suggest that pulmonary artery stenting with a short vascular sheath has numerous advantages and can be successfully performed in children. In the case of single-ventricle hearts after a Glenn procedure, it may indeed be the method of choice. © 2010 Via Medica.
Keywords: article; blood vessel diameter; child; clinical article; controlled study; Fallot tetralogy; female; Fontan procedure; Glenn shunt; heart single ventricle; human; hypoplastic left heart syndrome; infant; lung artery pressure; lung edema; male; Norwood procedure; percutaneous transluminal angioplasty; pulmonary artery stenosis; pulmonary artery stenting; stent; Williams Beuren syndrome; Coroflex; Genesis stent; Palmaz P-308 stent

Viral-associated trichodysplasia of immunosuppression: Report of a pediatric patient with response to oral valganciclovir - Benoit, T.; Bacelieri, R.; Morrell, D.S.; Metcalf, J. (Archives of Dermatology, 2010)
Background: Viral-associated trichodysplasia of immunosuppression is an increasingly recognized entity characterized by follicular-based papules, primarily in the central part of the face, that produce variable degrees of alopecia and dysmorphic features. It has been primarily described in transplant recipients but has recently been recognized in patients receiving chemotherapy for leukemia and lymphoma. It is associated with distinctive histologic features such as dilated anagen hair follicles, absent hair papillae, and abrupt cornification of the inner root sheath. Observations: A 5-year-old boy presented with spiny follicular papules that caused thickening of the skin of the face 1 year after cardiac transplantation. He had been exposed to several immunosuppressive agents, including mycophenolate mofetil, tacrolimus, intravenous immunoglobulin, rituximab, cylcophosphamide, and prednisone. Despite the failure of multiple topical treatments, our patient's eruption improved with systemic valganciclovir therapy. Conclusions: We describe the youngest patient (to our knowledge) with viral-associated trichodysplasia of immunosuppression and discuss the characteristic clinicopathologic features. Our report supports the theory that immunosuppression is the predisposing factor to a folliculotropic papovavirus that alters follicular maturation. ©2010 American Medical Association. All rights reserved.
Keywords: ammonium lactate; cidofovir; cyclophosphamide; eosin; hematoxylin; hyalin; immunoglobulin; inotropic agent; mycophenolate mofetil; prednisone; retinoic acid; rituximab; tacrolimus; tolonium chloride; triamcinolone; urea; valganciclovir; article; cardiac graft rejection; case report; cell nucleus; child; drug substitution; drug withdrawal; dysplasia; electron microscopy; erythema; face; fibrosis; general anesthesia; graft versus host reaction; heart transplantation; histiocyte; histology; histopathology; human; human tissue; hyperkeratosis; hypoplastic left heart syndrome; immunosuppressive treatment; Kabuki makeup syndrome; keratinocyte; keratosis; Darier disease; limb; lymphocytic infiltration; male; papovavirus; papule; plasmapheresis; preschool child; priority journal; pruritus; punch biopsy; skin biopsy; skinfold; staining; thigh; trunk; viral associated trichodysplasia of immunosuppression

Validation of the pediatric cardiac quality of life inventory - Marino, B.S.; Tomlinson, R.S.; Wernovsky, G.; Drotar, D.; Newburger, J.W.; Mahony, L.; Mussatto, K.; Tong, E.; Cohen, M.; Andersen, C.; Shera, D.; Khoury, P.R.; et al. (Pediatrics, 2010)
OBJECTIVE: The purpose of this multicenter study was to confirm the validity and reliability of the Pediatric Cardiac Quality of Life Inventory (PCQLI). METHODS: Seven centers recruited pediatric patients (8-18 years of age) with heart disease (HD) and their parents to complete the PCQLI and generic health-related quality of life (Pediatric Quality of Life Inventory [PedsQL]) and non-quality of life (Self-Perception Profile for Children [SPPC]/Self-Perception Profile for Adolescents [SPPA] and Youth Self-Report [YSR]/Child Behavior Checklist [CBCL]) tools. PCQLI construct validity was assessed through correlations of PCQLI scores between patients and parents and with severity of congenital HD, medical care utilization, and PedsQL, SPPC/SPPA, and YSR/CBCL scores. PCQLI test-retest reliability was evaluated. RESULTS: The study enrolled 1605 patient-parent pairs. Construct validity was substantiated by the association of lower PCQLI scores with Fontan palliation and increased numbers of cardiac operations, hospital admissions, and physician visits (P < .001); moderate to good correlations between patient and parent PCQLI scores (r = 0.41-0.61; P < .001); and fair to good correlations between PCQLI total scores and PedsQL total (r = 0.70-0.76), SPPC/SPPA global self-worth (r = 0.43-0.46), YSR/CBCL total competency (r = 0.28-0.37), and syndrome and Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition oriented scale (r = -0.58 to -0.30; P < .001) scores. Test-retest reliability correlations were excellent (r = 0.78-0.90; P < .001). CONCLUSIONS: PCQLI scores are valid and reliable for children and adolescents with congenital and acquired HD and may be useful for future research and clinical management. Copyright © 2010 by the American Academy of Pediatrics.
Keywords: adolescent; adult; aortic stenosis; aortic regurgitation; aortic valve stenosis; article; child; Child Behavior Checklist; clinical trial; competence; complete heart block; congenital heart disease; construct validity; coronary artery anomaly; correlation analysis; cross-sectional study; Diagnostic and Statistical Manual of Mental Disorders; disease severity; Ebstein anomaly; Fallot tetralogy; female; Fontan procedure; great vessels transposition; health care utilization; heart septum defect; heart surgery; hospital admission; human; hypoplastic left heart syndrome; major clinical study; male; medical research; mitral valve atresia; mitral valve prolapse; mitral valve regurgitation; mitral valve stenosis; multicenter study; assessment of humans; parent; patent ductus arteriosus; Pediatric Cardiac Quality of Life Inventory; physician; priority journal; prospective study; quality of life; rating scale; reliability; school child; scoring system; Self Perception Profile for Adolescents; Self Perception Profile for Children; self report; sinus node disease; supraventricular tachycardia; test retest reliability; tricuspid valve stenosis; validation study; Youth Self Report

Evaluating safety, effectiveness, and user satisfaction of home international normalized ratio monitoring service: Experience from a tertiary pediatric cardiology unit in the United Kingdom - Bhat, D.; Upponi, A.; Rakecha, A.; Thomson, J. (Pediatric Cardiology, 2010)
Home international normalized ratio (INR) monitors are being increasingly used for monitoring the adequacy of anticoagulation in children on long-term warfarin. Their safety and effectiveness in the home setting has not been fully established. The purpose of this study was to explore the safety and effectiveness of home INR monitoring service in managing anticoagulation in children with congenital heart disease. At the Pediatric Cardiology Regional Referral Center, we studied records of 41 children on warfarin and assessed the control of anticoagulation and frequency of adverse reactions over a 1-year period. User satisfaction was assessed by means of telephone interviews. The study found that the therapeutic INR range was maintained for over 57% of the total study period. There were no reported instances of major or minor hemorrhages. On six occasions, subtherapeutic INR levels necessitated hospitalization for heparinization. Mitral valve replacement was significantly associated with poor control (p < 0.05). User satisfaction was high for all aspects of the service evaluated. The hospital-assisted home INR monitoring service is a safe and effective means of managing anticoagulation in children. In addition, it ensures good compliance and a high level of user satisfaction. © 2009 Springer Science+Business Media, LLC.
Keywords: warfarin; adolescent; adult; anticoagulant therapy; aortic valve replacement; article; bleeding; child; clinical article; controlled study; drug indication; female; Fontan procedure; heparinization; home monitoring; hospitalization; human; international normalized ratio; interview; male; medical record review; mitral valve replacement; patient safety; patient satisfaction; preschool child; school child; United Kingdom

Discussion (Journal of Thoracic and Cardiovascular Surgery, 2010)
Keywords: abortion; algorithm; amniocentesis; article; autopsy; congenital heart malformation; conservative treatment; data base; heart surgery; heart transplantation; hospital; human; hypoplastic left heart syndrome; neonatology; newborn; newborn surgery; Norwood procedure; patient transport; priority journal; quality of life; Streptococcus infection; surgical mortality; surgical risk; survival; treatment outcome

Hypoplastic left heart syndrome in patients with Kabuki syndrome - Kung, G.C.; Chang, P.M.; Sklansky, M.S.; Randolph, L.M. (Pediatric Cardiology, 2010)
The association of cardiac defects with Kabuki syndrome has been well described. The majority of these defects are isolated shunt lesions, conotruncal abnormalities, or various forms of arch obstruction. This report describes a series of three patients with hypoplastic left heart syndrome and Kabuki syndrome. The series illustrates the full spectrum of left-sided obstructive lesions and expands the phenotype of cardiac defects associated with Kabuki syndrome. © 2009 Springer Science+Business Media, LLC.
Keywords: article; case report; child; enteric feeding; female; follow up; Fontan procedure; gastroesophageal reflux; Glenn shunt; human; hypoplastic left heart syndrome; infant; Kabuki makeup syndrome; male; microcephaly; nasogastric tube; Norwood procedure; preschool child; pulmonary hypertension; stomach tube; surgical approach

Hepatic adenomatosis in a 7-year-old child treated earlier with a fontan procedure - Babaoglu, K.; Binnetoglu, F.K.; Aydoǧan, A.; Altun, G.; Gürbüz, Y.; Inan, N.; Çorapçioǧlu, F. (Pediatric Cardiology, 2010)
Patients who undergo a Fontan procedure experience some degree of liver disease. Hemodynamic changes such as central venous hypertension, depressed dynamic cardiac output, and late ventricular dysfunction combined with long-standing hypoxia preceding the Fontan procedure all are recognized risk factors for hepatic injury. The histopathologic changes associated with cardiac hepatopathy include chronic passive congestion, centrilobular necrosis, and cardiac cirrhosis. However, hepatic adenoma and hepatic adenomatosis (HA) are not well-known pathologies during the course of cardiac hepatopathy. This study focused on a 7-year-old girl with chronic hepatic changes and HA who had undergone a Fontan procedure. Hepatic adenomatosis was diagnosed on the basis of magnetic resonance imaging (MRI) and MRI-guided liver biopsy. To the best of the authors' knowledge, this case involved the youngest patient with hepatocellular adenomatosis documented in the literature. It was a unique case because the patient experienced HA after a Fontan procedure. © 2010 Springer Science+Business Media, LLC.
Keywords: alanine aminotransferase; albumin; alkaline phosphatase; alpha fetoprotein; aspartate aminotransferase; bilirubin; bilirubin glucuronide; hemoglobin; protein; abdominal distension; adenomatosis; alanine aminotransferase blood level; albumin blood level; alkaline phosphatase blood level; angiocardiography; article; aspartate aminotransferase blood level; bilirubin blood level; case report; child; computer assisted tomography; cyanosis; Doppler ultrasonography; female; Fontan procedure; heart atrium septum defect; heart catheterization; hematocrit; hemoglobin blood level; hepatocellular adenomatosis; hepatomegaly; histopathology; human; human tissue; hypoplasia; inferior cava vein; leukocyte count; liver biopsy; liver cirrhosis; liver fibrosis; lung angiography; lung artery pressure; nuclear magnetic resonance imaging; oxygen saturation; partial thromboplastin time; postoperative complication; protein blood level; prothrombin time; pulmonary arteriovenous fistula; pulmonary valve atresia; school child; scoring system; staining; superior cava vein; platelet count; transcutaneous oxygen monitoring; tricuspid valve hypoplasia; umbilicus; venous pressure

Atrial Remodeling After the Fontan Operation - Wolf, C.M.; Seslar, S.P.; den Boer, K.; Juraszek, A.L.; McGowan, F.X.; Cowan, D.B.; Del Nido, P.; Triedman, J.K.; Berul, C.I.; Walsh, E.P. (American Journal of Cardiology, 2009)
The hemodynamics after Fontan surgery are notable for hypertension and dilation of the right atrium (RA). The effect of this stress on atrial cytoarchitecture has not been systematically studied and might be relevant to arrhythmias and their treatment. Morphologic and histopathologic analyses were performed on tissue from the RA and left atrium (LA) from autopsy specimens of Fontan hearts (n = 47). The findings were compared to those from control samples from young patients with normal atrial hemodynamics (n = 15). Most Fontan specimens were from young patients who died after a relatively short duration of Fontan physiology. The tissues were analyzed for wall thickness, fibrosis content, and fibrosis pattern. The mean wall thickness for the RA (3.0 ± 1.0 mm) and LA (2.3 ± 0.6 mm) in the Fontan hearts was significantly greater than that in the control hearts (RA, 1.8 ± 0.4 mm; LA, 1.8 ± 0.5 mm; p <0.001 and p = 0.024, respectively). The predictors for thickening of the RA included (1) older age at Fontan surgery, (2) older age at death, and (3) longer duration of Fontan circulation. The Fontan hearts and control hearts exhibited nearly identical fibrosis patterns in the RA and LA. Neither wall thickness nor fibrosis varied with the underlying heart defect or style of Fontan connection. In conclusion, atrial remodeling after Fontan surgery for univentricular heart physiology involves increased wall thickness in both the RA and LA. Interstitial fibrosis was also observed in the Fontan atria; however, because a similar pattern was present in the control tissue, this likely represented normal fibroelastic atrial structure, rather than a specific response to Fontan hemodynamics. The degree of wall thickening observed in the Fontan atria was not so excessive as to preclude transmural lesions during catheter or surgical ablation of reentrant arrhythmias. © 2009 Elsevier Inc. All rights reserved.
Keywords: adolescent; adult; aging; article; child; clinical article; controlled study; female; Fontan procedure; heart atrium arrhythmia; heart atrium muscle; heart atrium remodeling; heart hemodynamics; heart left atrium; heart muscle fibrosis; heart right atrium; heart single ventricle; histopathology; human; human tissue; infant; male; morphometry; priority journal; risk factor; surgical technique; thickness; tissue structure

Exercise capacity, quality of life, and daily activity in the long-term follow-up of patients with univentricular heart and total cavopulmonary connection - Müller, J.; Christov, F.; Schreiber, C.; Hess, J.; Hager, A. (European Heart Journal, 2009)
Aims Patients with congenital heart disease usually show diminished exercise capacity and quality of life. However, there is only little information about daily activity, a marker for lifestyle, exercise capacity, and the prevention of arteriosclerosis. This study investigated exercise capacity, quality of life, daily activity, and their interaction with univentricular heart physiology after total cavopulmonary connection (TCPC).Methods and resultsFifty-seven patients (18 females, 39 males, age 8-52 years) after TCPC (lateral tunnel 28, extra-cardiac conduit 29) who underwent surgery during 1994-2001 were examined in our institution. They performed a symptom-limited cardiopulmonary exercise test. Those patients 14 years of age and older filled in the health-related quality-of-life questionnaire SF-36, and those who were 8-13 years of age, the CF-87. Daily activity parameters were obtained by using a triaxial accelerometer over the next three consecutive days. Exercise capacity was severely reduced after TCPC (25.0 mL/min/kg corresponding to 59.7 of age-and sex-related reference values). Daily activity was within the recommendations of the United Kingdom Expert Consensus Group (≥60 min, ≥3 metabolic equivalent, ≥5 days/week) in 72 of the investigated patients. It was reduced in older patients (Spearman r =-0.506, P < 0.001) and patients with a lower peak oxygen uptake (Spearman r = 0.432, P = 0.001). In children <14 years, mental health was related to daily activity.ConclusionDespite their diminished exercise capacity, patients after TCPC show a fairly normal activity pattern. However, their activity depends not only on age, but also on exercise capacity, which, in contrast to healthy people, decreases already from early adolescence on.
Keywords: oxygen; accelerometer; adolescent; adult; age distribution; aged; article; cardiopulmonary exercise test; cavopulmonary connection; child; consensus; daily life activity; exercise; female; follow up; heart single ventricle; human; major clinical study; male; mental health; oxygen consumption; priority journal; quality of life; school child; sex difference; Short Form 36; United Kingdom

How Good Is a Good Fontan? Quality of Life and Exercise Capacity of Fontans Without Arrhythmias - d'Udekem, Y.; Cheung, M.M.H.; Setyapranata, S.; Iyengar, A.J.; Kelly, P.; Buckland, N.; Grigg, L.E.; Weintraub, R.G.; Vance, A.; Brizard, C.P.; Penny, D.J. (Annals of Thoracic Surgery, 2009)
Background: Poor long-term outcomes are expected after Fontan surgery, but these perspectives have been tainted by the poorly functioning Fontans suffering from arrhythmias. No predictions of outcome can be quoted to the increasing number of Fontan patients free from arrhythmic complications. The parameters determining improved exercise capacity and quality of life in this subgroup are yet unknown. Methods: Fontan survivors from our institution and living in Victoria were invited to participate in the study if they were more than 10 years of age, and free of arrhythmias. A mean of 17 ± 4 years after Fontan, 36 patients, 23 with a classical atriopulmonary connection (AP) and 13 with a lateral tunnel (LT) underwent transthoracic echocardiography, cycloergometer exercise study, neurohumoral screening, and assessment of quality of life. Results: The only factor predicting worse exercise capacity was the type of Fontan performed; patients with LT having better exercise capacity than those with AP (percentage of predicted anaerobic threshold: 88 ± 14% vs 72 ± 14%, p < 0.005; percentage of predicted Vo2max: 62 ± 8% vs 54 ± 7%, p < 0.005). Endothelin-1 levels were elevated in all patients (2.9 pmol/L, 2.5 to 3.7). Responses from the quality of life measures placed our Fontan cohort mainly within the normal population range. None of the preoperative and postoperative variables adversely affected patients' quality of life. Conclusions: The anaerobic threshold of arrhythmia-free Fontan patients operated with the lateral tunnel technique was relatively preserved. Despite restricted exercise capacity, Fontan patients, provided that they are free of arrhythmias, have a normal quality of life reflected in their reports of psychiatric symptoms and family relationships. © 2009 The Society of Thoracic Surgeons.
Keywords: endothelin 1; adolescent; anaerobic threshold; article; atriopulmonary connection; child; clinical article; cohort analysis; controlled study; ergometer; exercise; female; Fontan procedure; heart arrhythmia; human; male; population; prediction; preoperative evaluation; preschool child; priority journal; quality of life; school child; screening; survivor; transthoracic echocardiography

The oxidative state of children with cyanotic and acyanotic congenital heart disease - Ercan, S.; Çakmak, A.; Kösecik, M.; Erel, Ö. (Anadolu Kardiyoloji Dergisi, 2009)
Objective: The type of congenital heart disease, early diagnosis, and treatment modality all play an important role in the morbidity and mortality of these diseases. This study examined the relationship between congenital heart disease and oxidative stress in children with cyanotic and acyanotic congenital heart disease. Methods: In this case-controlled cross-sectional study, the study groups consisted of 29 patients with cyanotic heart disease, 30 patients with acyanotic heart disease, and a control group of 32 healthy individuals. For all groups, the total oxidant status (TOS), total antioxidant status (TAS), and oxidative stress index (OSI) were calculated. Of the cyanotic group, 12 were diagnosed with tetralogy of Fallot, 7 with transposition of the great arteries, 4 with tricuspid atresia, 4 with double outlet right ventricle and 2 with truncus arteriosus. In the acyanotic group 19 patients had ventricular septal defect (VSD), 5 atrial septal defect (ASD) and 6 patent ductus arteriosus (PDA). Statistical analyses were performed using Chi-square, Mann-Whitney U and Kruskal-Wallis tests. Results: The plasma TAS, TOS, and OSI were significantly higher in the cyanotic group than in the acyanotic group (p<0.0001, p<0.01, and p<0.01, respectively) and controls (p<0.0001, p<0.0001, and p<0.0001, respectively). A comparison between the acyanotic and control groups showed no statistical differences. Conclusion: The level of oxidative stress in patients with cyanotic congenital heart disease was significantly higher than in the acyanotic and control groups, which were similar. ©Copyright 2009 by AVES Yayincilik Ltd.
Keywords: antioxidant; antioxidant activity; arterial trunk; article; chi square test; child; controlled study; cross-sectional study; cyanotic heart disease; Fallot tetralogy; female; heart atrium septum defect; heart disease; heart right ventricle double outlet; heart ventricle septum defect; human; infant; Kruskal Wallis test; major clinical study; male; morbidity; mortality; newborn; oxidative stress; patent ductus arteriosus; preschool child; rank sum test; statistical analysis; statistical significance; tricuspid valve atresia

Is "Treat your child normally" helpful advice for parents of survivors of treatment of hypoplastic left heart syndrome? - Rempel, G.R.; Harrison, M.J.; Williamson, D.L. (Cardiology in the Young, 2009)
Background: Developing technology affords children with complex congenitally malformed hearts a chance for survival. Parents gratefully pursue life-saving options on behalf of their children, despite the risks to the life of their child, and uncertainty about outcomes. Little is known about how mothers and fathers experience parenting a child whose new state as a survivor may include less than optimal developmental sequels. Method: Our study involved multiple interactive interviews with 9 mothers and 7 fathers of infants and preschool children with hypoplastic left heart syndrome who had survived the Norwood surgical approach. Qualitative methodology included grounded theory methods of simultaneous collection and analysis of data, and we used open and selective coding of transcribed interviews. Results: Parents used normalization in the context of uncertainty regarding the ongoing survival of their child. Parents described their underweight children as being on their own growth curve, and viewed their developmental progress, however delayed, as reason for celebration, as they had been prepared for their child to die. Conclusion: There is growing evidence that children with congenitally malformed hearts who require surgical intervention during the first year of life may experience developmental delay. The use of normalization by their parents may be effective in decreasing their worry regarding the uncertain future faced by their child, but may negatively affect the developmental progress of the child if they do not seek resources to assist development. Advice from paediatric specialists for parents to view their children as normal needs to be balanced with assistance for parents to access services to support optimal growth and development of their child. Copyright © Cambridge University Press 2009.
Keywords: article; attitude to death; child; child care; child growth; child parent relation; clinical article; developmental disorder; female; growth curve; heart surgery; human; hypoplastic left heart syndrome; infant; interview; male; parental attitude; parenting education; preschool child; qualitative research; surgical technology; survivor; underweight

The effect of bosentan in patients with a failing Fontan circulation - Ovaert, C.; Thijs, D.; Dewolf, D.; Ottenkamp, J.; Dessy, H.; Moons, P.; Gewillig, M.; Mertens, L. (Cardiology in the Young, 2009)
Objectives: To investigate the effect of bosentan in patients with a failing Fontan circulation. Design: A multicentric open label, non-controlled study. Setting: 5 tertiary care centres for congenital cardiology. Patients: We included 10 patients with a failing Fontan circulation. Their median age at inclusion was 12.12 years, with a range from 4.41 to 33,41 years. The median interval between the Fontan operation and inclusion was 7.84 years, with a range from 1.96 to 12,18 years. Participants received half the usual dose of bosentan for 4 weeks, and then the full dose for a further 12 weeks. Main measures of outcomes: We assessed saturations of oxygen at rest and during exercise, using a 6 minutes walk test, at baseline, and during and after 16 weeks of treatment. At each visit, we assessed blood chemistry and hepatic function, and asked the patients to complete a questionnaire concerning quality of life. All medical events and possible side effects were recorded. Results: Of the cohort, 1 patient withdrew. The changes in saturations of oxygen, exercise performance, and scores for the questionnaire did not reach statistical significance for the whole group. We noted, nonetheless, that saturations of oxygen and/or exercise capacity improved in 5 of the patients. This was further confirmed when those patients deteriorated again when the drug was discontinued. Conclusions: Our study failed to show significant improvement after 3 months of treatment with bosentan in a small group of patients with failing Fontan circulations. Some individuals, nonetheless, did improve. When planning larger trials, it would be better to identify those patients who might potentially benefit from the treatment prior to commencing the trial. © 2009 Copyright © Cambridge University Press 2009.
Keywords: aciclovir; amoxicillin; anticoagulant agent; antithrombocytic agent; bosentan; dipeptidyl carboxypeptidase inhibitor; diuretic agent; meprednisone; vasodilator agent; adolescent; adult; age distribution; article; blood chemistry; child; clinical article; clinical trial; cyanosis; dose response; drug tolerability; drug withdrawal; edema; exercise; fatigue; female; fever; Fontan procedure; heart hemodynamics; herpes labialis; human; ischemia; liver function; male; multicenter study; oxygen consumption; oxygen saturation; protein losing gastroenteropathy; quality of life; questionnaire; side effect; tertiary health care; treatment failure; upper respiratory tract infection; venous congestion; virus reactivation; walking; body weight gain

Parent- versus child-reported functional health status after the fontan procedure - Lambert, L.M.; Minich, L.L.; Newburger, J.W.; Lu, M.; Pemberton, V.L.; McGrath, E.A.; Atz, A.M.; Mingfen, X.; Radojewski, E.; Servedio, D.; McCrindle, B.W. (Pediatrics, 2009)
OBJECTIVE: We sought to compare perceptions of functional health status between children who had undergone a Fontan procedure and their parents. METHODS: Fontan procedure survivors 10 to 18 years of age were included in the study if the child completed the Child Health Questionnaire (CHQ) and the parent completed the parent form to assess the child's functional health status. Comparisons were made between raw domain scores for the parent- and child-completed CHQs. RESULTS: Between March 2003 and April 2004, 1078 Fontan survivors were screened. Of the 546 eligible and consented patients, 354 were 10 -18 years of age and 328 parent/child pairs completed the CHQs. Parents reported significantly lower scores (worse functioning) for their children than the children reported for themselves in the domains of physical functioning (P < .01), impact on school or activities from emotional and behavioral problems (P < .01), impact on school or activities from physical health issues (P<.01), general behavior (P < .01), mental health (P < .01), self-esteem (P < .01), and general health perceptions (P<.01). No significant differences were noted for the domains of bodily pain, family cohesiveness, or family activities. For the physical functioning domain, factors contributing to lower scores for parent versus child reports included pulmonary artery anomalies and fenestration at the time of the Fontan operation. Lower parent-reported scores also were associated with more noncardiac health problems in the child. CONCLUSIONS: Parents' perceptions of the functional health status of their children after the Fontan procedure were worse than the children's perceptions. Copyright © 2009 by the American Academy of Pediatrics.
Keywords: dipeptidyl carboxypeptidase inhibitor; adult; article; attitude to health; behavior disorder; child; child health; controlled study; emotional disorder; female; fenestration; Fontan procedure; health; health status; heart catheterization; human; male; mental health; pain; parental attitude; patient attitude; priority journal; pulmonary artery malformation; questionnaire; school child; self esteem

Intravascular mechanical cavopulmonary assistance for patients with failing fontan physiology - Bhavsar, S.S.; Kapadia, J.Y.; Chopski, S.G.; Throckmorton, A.L. (Artificial Organs, 2009)
To provide a viable bridge-to-transplant, bridge-to-recovery, or bridge-to-surgical reconstruction for patients with failing Fontan physiology, we are developing a collapsible, percutaneously inserted, magnetically levitated axial flow blood pump to support the cavopulmonary circulation in adolescent and adult patients. This unique blood pump will augment pressure and thus flow in the inferior vena cava through the lungs and ameliorate the poor hemodynamics associated with the univentricular circulation. Computational fluid dynamics analyses were performed to create the design of the impeller, the protective cage of filaments, and the set of diffuser blades for our axial flow blood pump. These analyses included the generation of pressure-flow characteristics, scalar stress estimations, and blood damage indexes. A quasi-steady analysis of the diffuser rotation was also completed and indicated an optimal diffuser rotational orientation of approximately 12°. The numerical predictions of the pump performance demonstrated a pressure generation of 2-25 mm Hg for 1-7 L/min over 3000-8000 rpm. Scalar stress values were less than 200 Pa, and fluid residence times were found to be within acceptable ranges being less than 0.25 s. The maximum blood damage index was calculated to be 0.068%. These results support the continued design and development of this cavopulmonary assist device, building upon previous numerical work and experimental prototype testing. © 2009, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: article; blood pressure; blood pump; computational fluid dynamics; Fontan procedure; heart assist device; inferior cava vein; lung blood flow; lung circulation; lung hemodynamics; mathematical model; pressure measurement; priority journal; quasi experimental study; surgical technique; treatment failure; vascular disease

Pulsatile in vitro simulation of the pediatric univentricular circulation for evaluation of cardiopulmonary assist scenarios - Dur, O.; Lara, M.; Arnold, D.; Vandenberghe, S.; Keller, B.B.; Degroff, C.; Pekkan, K. (Artificial Organs, 2009)
The characteristic depressed hemodynamic state and gradually declining circulatory function in Fontan patients necessitates alternative postoperative management strategies incorporating a system level approach. In this study, the single-ventricle Fontan circulation is modeled by constructing a practical in vitro bench-top pulsatile pediatric flow loop which demonstrates the ability to simulate a wide range of clinical scenarios. The aim of this study is to illustrate the utility of a novel single-ventricle flow loop to study mechanical cardiac assist to Fontan circulation to aid postoperative management and clinical decision-making of single ventricle patients. Two different pediatric ventricular assist devices, Medos and Pediaflow Gen-0, are anastomosed in two nontraditional configurations: systemic venous booster (SVB) and pulmonary arterial booster (PAB). Optimum ventricle assist device strategy is analyzed under normal and pathological (pulmonary hypertension) conditions. Our findings indicate that the Medos ventricular assist device in SVB configuration provided the highest increase in pulmonary (46%) and systemic (90%) venous flow under normal conditions, whereas for the hypertensive condition, highest pulmonary (28%) and systemic (55%) venous flow augmentation were observed for the Pediaflow ventricular assist device inserted as a PAB. We conclude that mechanical cardiac assist in the Fontan circulation effectively results in flow augmentation and introduces various control modalities that can facilitate patient management. Assisted circulation therapies targeting single-ventricle circuits should consider disease state specific physiology and hemodynamics on the optimal configuration decisions. © 2009, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: article; assisted circulation; blood vessel compliance; clinical decision making; controlled study; Fontan procedure; heart assist device; heart left ventricle pressure; heart single ventricle; hemodynamics; hypertension; in vitro study; patient care; postoperative period; priority journal; pulmonary hypertension; pulsatile flow; simulation; vascular resistance; vein blood flow; Medos; Pediaflow

Clinical outcomes of Fontan conversion surgery with and without associated arrhythmia intervention - Takahashi, K.; Fynn-Thompson, F.; Cecchin, F.; Khairy, P.; del Nido, P.; Triedman, J.K. (International Journal of Cardiology, 2009)
Objective: To characterize mortality and morbidity outcomes in patients undergoing surgical Fontan conversion. Background: Indications for and anticipated clinical outcomes associated with Fontan conversion are controversial. Methods: A retrospective single-center cohort study of consecutive patients undergoing Fontan conversion between 1990 and 2006 stratified according to concomitant arrhythmia surgery. Results: Forty patients underwent Fontan conversion at a median age of 19.0 years and were followed for 4.2 years. Six (15%) died, two perioperatively, three early postoperatively, and one following heart transplant. Older age was a univariate risk factor. Major perioperative complications occurred in 9 of 35 (26%) early survivors. Patients with concomitant arrhythmia surgery (N = 21) were older at conversion and had longer interoperative intervals. They experienced a reduction in prevalence (95% vs. 28%, P < 0.0001) and severity (severity score 7.3 vs. 3.3, P = 0.001) of atrial tachyarrhythmias, in contrast to patients without arrhythmia surgery (47% vs. 53%; 3.3 vs. 3.9, P = NS). NYHA functional class improved in both groups. In a subgroup (N = 14) with non-urgent late postoperative catheterization, filling pressures were unchanged from preoperative values. Conclusions: Mortality and morbidity after Fontan conversion are substantial, but survivors experience a subjective improvement in functional status. Concomitant arrhythmia surgery reduces the arrhythmia burden without a detectable increase in complication rates. © 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: antiarrhythmic agent; adolescent; adult; article; brain hemorrhage; cerebrovascular accident; clinical article; cohort analysis; disease severity; follow up; Fontan procedure; functional assessment; gastrointestinal hemorrhage; heart atrium arrhythmia; heart atrium thrombosis; heart catheterization; heart surgery; heart transplantation; hematothorax; human; intracardiac thrombosis; kidney dysfunction; morbidity; mortality; multiple organ failure; outcome assessment; peroperative complication; perioperative period; peritoneal dialysis; pleura effusion; postoperative care; postoperative hemorrhage; postoperative period; prevalence; priority journal; retrospective study; risk factor; risk reduction; scoring system; seizure; supraventricular tachycardia; survivor; treatment outcome

Improved management of systemic venous anomalies in a single ventricle: New rationale - Amodeo, A.; Grigioni, M.; Filippelli, S.; Gagliardi, M.G.; Del Gaudio, C.; Morbiducci, U.; D'Avenio, G.; Brancaccio, G.; Di Donato, R.M. (Journal of Thoracic and Cardiovascular Surgery, 2009)
Objectives: Two innovative surgical approaches addressing systemic venous anomalies in single-ventricle patients are evaluated. Methods: Between 2003 and 2007, 7 patients underwent a unifocal bilateral bidirectional cavopulmonary anastomosis, and 5 patients underwent a hepatoazygos venous connection associated with a previous (n = 4) or concomitant (n = 1) Kawashima operation. Computational fluid dynamics simulations allowed investigation of 2 sets of comparative models: (1) bifocal versus unifocal bilateral bidirectional cavopulmonary anastomosis and (2) classic hepatic vein-pulmonary artery channel versus hepatoazygos direct anastomosis for Fontan completion after or combined with the Kawashima operation. Results: There was 1 hospital death in the unifocal bilateral bidirectional cavopulmonary anastomosis group. At a mean follow-up of 15.6 ± 7.40 months after a unifocal bilateral bidirectional cavopulmonary anastomosis and of 38.7 ± 13.2 months after direct hepatoazygos venous connection, respectively, all 11 survivors are in New York Heart Association class I with functional anastomoses. Computational assessment of bifocal bilateral bidirectional cavopulmonary anastomosis demonstrated weak perfusion between caval veins against symmetric and steady bilateral flow fields in the unifocal arrangement. In the classic post-Kawashima Fontan completion model, the hepatic venous flow to the pulmonary artery was held back by means of preponderant opposite flow, whereas in the direct hepatoazygos venous connection model, the hepatic venous flow merged smoothly into the azygos vein. Power-loss calculation showed no significant difference between bifocal and unifocal bilateral bidirectional cavopulmonary anastomosis topology, whereas the hepatoazygos connection clearly had better energy preservation than the classical connection. Conclusions: This limited clinical and computational fluid dynamics assessment suggests the efficacy of this new rationale to reduce the additional thrombotic risks produced by systemic venous anomalies in single-ventricle patients. © 2009 The American Association for Thoracic Surgery.
Keywords: article; cava vein; cavopulmonary connection; child; clinical article; follow up; Fontan procedure; heart single ventricle; human; infant; mathematical computing; perfusion; priority journal; pulmonary artery; risk reduction; simulation; surgical approach; surgical technique; thrombosis; vein malformation

Development of a pediatric cardiology quality improvement collaborative: From inception to implementation. From the joint council on congenital heart disease quality Improvement task force - Kugler, J.D.; Beekmani III, R.H.; Rosenthal, G.L.; Jenkins, K.J.; Klitzner, T.S.; Martin, G.R.; Neish, S.R.; Lannon, C. (Congenital Heart Disease, 2009)
While clinical outcomes in pediatric cardiac disease have improved in recent years, marked institutional and individual cardiology practice variability exists. Quality improvement science has demonstrated that reducing process variation leads to more favorable outcomes, safer practices, cost savings, and improved operating efficiency. This report describes the process undertaken to develop the first collaborative quality improvement project of the Joint Council on Congenital Heart Disease. The project chosen aims to reduce mortality and improve the quality of life of infants with hypoplastic left heart syndrome during the interstage period between discharge from the Norwood procedure and admission for the bidirectional Glenn procedure. The objective of this special article is to inform the pediatric cardiology and cardiac surgery communities of the project to help ensure that the early work by the project pilot participants will spread to clinicians caring for children with cardiovascular disease. It is anticipated that this project will add to our understanding of care for this challenging group of children with hypoplastic left heart syndrome, identifying clinical care changes with the potential to lead to improvements in outcome. It will also introduce the field of pediatric cardiology to the science of collaborative quality improvement and assist in reducing clinical process variation and improving patient outcomes across centers. Finally, it will establish an ongoing network of pediatric cardiologists and their teams linked through a longitudinal data set and collaboration for improvement and research. © 2009 Copyright the Author Journal compilation © 2009 Wiley Periodicals, Inc.
Keywords: article; cardiovascular disease; child health care; child nutrition; clinical protocol; consensus development; data base; disease surveillance; funding; health care quality; health center; health program; hypoplastic left heart syndrome; information dissemination; medical informatics; parental behavior; participatory management; patient monitoring; pediatric cardiology; priority journal; prognosis; registration; total quality management; treatment planning

A multicentric study of disease-related stress, and perceived vulnerability, in parents of children with congenital cardiac disease - Vrijmoet-Wiersma, C.M.J.; Ottenkamp, J.; Van Roozendaal, M.; Grootenhuis, M.A.; Koopman, H.M. (Cardiology in the Young, 2009)
Parents of children with congenitally malformed hearts can suffer from stress as a result of the medical condition of their child. In this cross-sectional study, we aimed to describe levels of parental stress, and perceived vulnerability, in parents of children who underwent major cardiac surgery, by using both generic and disease-related measures for assessment. We included parents of children who underwent open-heart surgery over the period 2002 through 2007 in the Center for congenital Anomalies Heart Amsterdam/Leiden, abbreviated to provide the acronym CAHAL. In total, we assessed 114 mothers and 82 fathers of 131 children, using the Pediatric Inventory for Parents, short form, General Health Questionnaire, Parental Stress Index-Short Form, State-Trait Anxiety Index and the Child Vulnerability Scale. Compared to the reference groups of the instruments used, parents of children with congenitally malformed hearts did not report higher generic nor disease-related stress scores, and parenting levels of stress were also comparable to reference groups. State anxiety levels, however, were higher in mothers of children with congenitally malformed hearts. Both fathers and mothers reported significantly higher rates of perceived vulnerability than did parents of healthy children. Risk factors for increased anxiety and perceived vulnerability were found in the number of surgical procedures, the time past since the last procedure, and ethnicity. Severity of the lesion did not influence parental levels of stress, but parents of children with hypoplastic left heart syndrome did report higher levels of stress than other parents. Psychosocial screening of parents of children with congenitally malformed hearts is important in order to provide appropriate counselling to those parents most in need. © 2009 Cambridge University Press.
Keywords: adult; anxiety; article; child; child parent relation; congenital heart malformation; controlled study; disease severity; ethnicity; female; General Health Questionnaire; human; hypoplastic left heart syndrome; infant; major clinical study; male; open heart surgery; parental stress; preschool child; risk factor; school child; scoring system; State Trait Anxiety Inventory; vulnerable population

Clinical profiles of adult patients with single ventricular physiology - Motoki, N.; Ohuchi, H.; Miyazaki, A.; Yamada, O. (Circulation Journal, 2009)
Background: This study was performed to clarify the present global clinical status, including medication(s) and social abilities, of adult patients with single ventricular physiology (SVP). Methods and Results: Clinical charts were retrospectively reviewed to evaluate the global clinical status, including functional capacity, medication(s), complications, and social activities of 68 adult patients with SVP aged 20-53 years (41 males); 50 had undergone the Fontan operation and they were divided into the young adult (25 patients) and adult Fontan groups. The others were cyanotic patients without the Fontan operation (non-Fontan group). Although the Fontan groups showed better functional capacity, higher arterial oxygen saturation and brain natriuretic peptide levels, and a better renal function, there was no difference in the cardiovascular events during follow-up between the 3 groups. The most frequent complication was arrhythmia without a significant group difference, although the non-Fontan group showed a high percentage of heart failure. Only 41 patients (60%) had a job and 8 (12%) were married. Conclusions: Although the Fontan groups had favorable pathophysiological conditions, the high rate of cardiovascular events, as well as unsatisfactory social situations, indicate the importance of meticulous life-long management of patients with SVP, regardless of the type of surgical intervention.
Keywords: angiotensin receptor antagonist; antiarrhythmic agent; anticoagulant agent; anticonvulsive agent; beta adrenergic receptor blocking agent; brain natriuretic peptide; carvedilol; creatinine; digoxin; dipeptidyl carboxypeptidase inhibitor; diuretic agent; hemoglobin; metoprolol; nitrogen; propranolol; urea; uric acid; adult; age distribution; arterial oxygen saturation; article; bacterial endocarditis; bradycardia; brain abscess; cardiovascular disease; central venous pressure; controlled study; creatinine blood level; female; follow up; Fontan procedure; functional status; glomerulus filtration; gout; health status; heart arrhythmia; heart ejection fraction; heart failure; cardiac index; heart single ventricle; heart ventricle enddiastolic pressure; heart ventricle pressure; heart ventricle tachycardia; hemoglobin blood level; hemoptysis; human; kidney function; long term care; major clinical study; male; marriage; medical record review; occupation; oxygen consumption; pathophysiology; protein blood level; protein losing gastroenteropathy; retrospective study; social behavior; supraventricular tachycardia; thrombus; urea nitrogen blood level; uric acid blood level

Are birth defects among hispanics related to maternal nativity or number of years lived in the United States? - Ramadhani, T.; Short, V.; Canfield, M.A.; Waller, D.K.; Correa, A.; Royle, M.; Scheuerle, A. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2009)
BACKGROUND: Literature on the risk of birth defects among foreign- versus U.S.-born Hispanics is limited or inconsistent. We examined the association between country of birth, immigration patterns, and birth defects among Hispanic mothers. METHODS: We used data from the National Birth Defects Prevention Study and calculated odds ratios (ORs) and 95% confidence intervals and assessed the relationship between mothers' country of birth, years lived in the United States, and birth defects among 575 foreign-born compared to 539 U.S.-born Hispanic mothers. RESULTS: Hispanic mothers born in Mexico/Central America were more likely to deliver babies with spina bifida (OR = 1.53) than their U.S.-born counterparts. Also, mothers born in Mexico/Central America or who were recent United States immigrants (≤5 years) were less likely to deliver babies with all atrial septal defects combined, all septal defects combined, or atrial septal defect, secundum type. However, Hispanic foreign-born mothers who lived in the United States for >5 years were more likely to deliver babies with all neural tube defects combined (OR = 1.42), spina bifida (OR = 1.89), and longitudinal limb defects (OR = 2.34). Foreign-born mothers, regardless of their number of years lived in the United States, were more likely to deliver babies with anotia or microtia. CONCLUSIONS: Depending on the type of birth defect, foreign-born Hispanic mothers might be at higher or lower risk of delivering babies with the defects. The differences might reflect variations in predisposition, cultural norms, behavioral characteristics, and/or ascertainment of the birth defects. © 2009 Wiley-Liss, Inc.
Keywords: adult; anencephalus; anus atresia; aortic coarctation; aortic stenosis; article; ataxia; baby; behavior; congenital malformation; Central America; cleft lip; cleft palate; comparative study; controlled study; craniofacial synostosis; obstetric delivery; diaphragm hernia; disease association; disease predisposition; esophagus atresia; Fallot tetralogy; female; gastroschisis; genetic variability; gestational age; great vessels transposition; heart atrium septum defect; heart left ventricle outflow tract obstruction; heart right ventricle outflow tract obstruction; heart septum defect; heart ventricle septum defect; Hispanic; human; hypoplastic left heart syndrome; hypospadias; immigration; infant; limb defect; longitudinal study; lung vein drainage anomaly; major clinical study; male; maternal age; Mexico; microtia; mother; neural tube defect; omphalocele; priority journal; pulmonary valve stenosis; risk; spinal dysraphism; United States

Hypoplastic Left Heart Syndrome: A Paradigm Case for Examining Conscientious Objection in Pediatric Practice - Ross, L.F.; Frader, J. (Journal of Pediatrics, 2009)
Keywords: article; child health care; genetic disorder; heart transplantation; human; hypoplastic left heart syndrome; life extension; medical decision making; medical ethics; medical practice; palliative therapy; priority journal; quality of life; risk factor; survival rate

Do neonates with genetic abnormalities have an increased morbidity and mortality following cardiac surgery? - Simsic, J.M.; Coleman, K.; Maher, K.O.; Cuadrado, A.; Kirshbom, P.M. (Congenital Heart Disease, 2009)
Introduction. Genetic abnormalities occur in approximately 20% of children with congenital heart disease. The purpose of this study was to evaluate the effect of genetic abnormalities on short-term outcomes following neonatal cardiac surgery. Methods. Retrospective review of all neonates (n = 609) undergoing cardiac surgery from January 2003 to December 2006. Genetic abnormalities were identified in 93 neonates (15%). Genetic abnormalities identified were 22q11.2 deletion (23), chromosomal abnormalities including various monosomies, trisomies, deletions, duplications, and inversions (17), dysmorphic undefined syndrome without recognized chromosomal abnormality (27), Down syndrome (9), laterality sequences (9), recognixed syndromes and genetic etiology including Mendelian (i.e. Alagille, CHARGE) (8). Results. Neonates with genetic abnormalities had lower birth weights and were older at time of surgery. There was no difference in operative variables, duration of mechanical ventilation or ICU length of stay between the two groups. There was an increase in total hospital length of stay and postoperative complications in the neonates with genetic abnormalities. Importantly, in hospital mortality was not different. Conclusion. Neonates with genetic abnormalities have a higher risk of postoperative complications and a longer hospital length of stay. However, there is no increase in hospital mortality. This information may aid in patient management decisions and parental counseling. Longer-term studies are needed for understanding the total impact of genetic abnormalities on neonates with congenital heart disease. © Journal compilation © 2009 Wiley Periodicals, Inc.
Keywords: aortic coarctation; article; artificial ventilation; body dysmorphic disorder; cardiopulmonary bypass; chromosome 22q; chromosome deletion; chromosome duplication; chromosome inversion; congenital heart disease; DiGeorge syndrome; Down syndrome; enteric feeding; Fallot tetralogy; feeding disorder; genetic disorder; heart arrhythmia; heart surgery; heart ventricle septum defect; human; hypoplastic left heart syndrome; intensive care unit; length of stay; low birth weight; monosomy; newborn; newborn morbidity; newborn mortality; parent counseling; pericardial effusion; postoperative complication; priority journal; pulmonary valve atresia; reoperation; risk factor; trisomy

Identification of second trimester screen positive pregnancies at increased risk for congenital heart defects - Jelliffe-Pawlowski, L.L.; Walton-Haynes, L.; Currier, R.J. (Prenatal Diagnosis, 2009)
Objective: To examine whether second trimester biomarkers could be used to identify screen positive pregnancies at increased risk for congenital heart defects (CHDs) and measure the effect of using different biomarker cut points on the detection of CHDs and on the performance of predictive models. Methods: Included were 19,402 pregnancies without chromosomal defects, which were screen positive for Down syndrome or other birth defects based on maternal serum measurements of alpha-fetoprotein (AFP), human chorionic gonadotrophin (hCG), and unconjugated estriol (uE3). Logistic regression models were built that compared biomarkers for CHD cases compared to controls. Results: CHD cases were more likely to be screen positive for trisomy-18, to have a nuchal fold (NF) ≥5 mm, and/or to have an hCG multiple of the median (MoM) ≥95th percentile in models that considered screen positive grouping. In models that did not consider screen positive grouping, cases were more likely to have a NF ≥5 mm, an AFP MoM ≤10th percentile, an hCG MoM ≤25th percentile, and/or an hCG MoM ≥75th percentile. Conclusion: Along with NF, second trimester maternal serum biomarkers may be useful indicators for fetal and newborn evaluation for CHDs in screen positive pregnancies without identified chromosomal defects. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: alpha fetoprotein; chorionic gonadotropin; estriol; adult; aortic coarctation; article; congenital malformation; congenital heart malformation; controlled study; Down syndrome; endocardial cushion defect; Fallot tetralogy; female; fetus; fetus echography; genetic counseling; heart atrium septum defect; heart ventricle septum defect; high risk pregnancy; human; hypoplastic left heart syndrome; maternal serum; neural tube defect; newborn; nuchal translucency measurement; patent ductus arteriosus; pregnancy outcome; prenatal care; prenatal screening; priority journal; pulmonary valve disease; second trimester pregnancy; tricuspid valve atresia; tricuspid valve stenosis; trisomy 18

Pediatric cardiac care consortium: An instrument for evidence-based clinical decision support - Pyles, L.A.; Hills, C.M.; Larson, V.E.; Moller, J.H. (Journal of Cardiovascular Translational Research, 2009)
Pediatric Cardiac Care Consortium is a registry of cardiac catheterizations, surgical operations, and autopsies performed for infants, children, and adults with congenital heart disease. Four examples of use of PCCC data to evaluate variability in morphology, management, and outcomes for the procedures are described. Consideration is given to the following clinical problems: (1) the experience with surgical heart block in operative closure of perimembranous VSD, (2) the transition away from atrial baffle operations to the arterial switch operation for simple transposition of the great arteries, (3) the experience of planned 3 stage palliation of hypoplastic left heart syndrome, and (4) the identification of a high risk combination of cardiovascular anomalies in Williams syndrome. Analysis of registry outcomes allows ongoing quality improvement at a cardiac center to consider not only its own experience but that of the overall group. The PCCC data can be used to personalize management of rare congenital cardiac anomalies and combinations of anomalies. The PCCC registry allows longitudinal consideration of issues such as staged repairs and incidence of unplanned reoperation. In future years, the PCCC can facilitate investigations into the etiology of congenital heart disease. © 2009 Springer Science+Business Media, LLC.
Keywords: adolescent; adult; article; child care; decision support system; evidence based medicine; heart block; heart function; human; hypoplastic left heart syndrome; major clinical study; priority journal; Williams Beuren syndrome

Physical activity restrictions for children after the Fontan operation: Disagreement between parent, cardiologist, and medical record reports - Longmuir, P.E.; McCrindle, B.W. (American Heart Journal, 2009)
Background: Physical activity is important for the health of children after the Fontan procedure. Parents uncertain about physical activity have children who are more sedentary. To understand parent uncertainty, we examined agreement regarding activity restrictions from parents, cardiologists, and medical charts. Methods: Activity restriction information for 64 children (25 female), 6 to 11 years, with a Fontan circulation was obtained via cardiologist and parent questionnaire. Each child's medical chart was reviewed for relevant physical activity information. κ Statistics calculated agreement between sources beyond chance. Results: Cardiologist, parent, and medical chart reports of the child's activity restrictions often disagree. Regardless of the cardiologist reported restrictions, 70% of parents reported that their child's activity was restricted (κ = 0.04, P = .25). Parents and cardiologists report the same body contact restrictions (κ = 0.16) but differ for exertion and competition (κ < .05) restrictions. Medical charts reflect competitive sport (κ = 0.26) but not body contact or exertion restrictions. Conclusions: Parent feelings of uncertainty about physical activity are supported by these results indicating that reports of activity restrictions after the Fontan procedure vary significantly by source. Parent and cardiologist reports agree only for body contact restrictions due to anticoagulation therapy. Exertion and body contact restrictions are not reflected in clinic letters to primary care providers. Ensuring that activity restrictions are accurately conveyed will enable parents and primary care providers to confidently encourage the active lifestyles that are so important for these children. © 2009 Mosby, Inc. All rights reserved.
Keywords: anticoagulant therapy; article; cardiologist; caregiver; child; female; Fontan procedure; human; lifestyle; major clinical study; male; medical record; parent; parent counseling; physical activity; priority journal; questionnaire; school child; sport

Extracardiac lesions and chromosomal abnormalities associated with major fetal heart defects: Comparison of intrauterine, postnatal and postmortem diagnoses - Song, M.S.; Hu, A.; Dyhamenahali, U.; Chitayat, D.; Winsor, E.J.T.; Ryan, G.; Smallhorn, J.; Barrett, J.; Yoo, S.-J.; Hornberger, L.K. (Ultrasound in Obstetrics and Gynecology, 2009)
Objectives The clinical outcome of prenatally diagnosed congenital heart defects (CHD) continues to be affected significantly by associated extracardiac and chromosomal abnormalities. We sought to: determine the frequency and type of major extracardiac abnormalities (with impact on quality of life) and chromosomal abnormalities associated with fetal CHD; and compare the extracardiac abnormalities detected prenatally to the postnatal and autopsy findings in affected fetuses, to find the incidence of extracardiac abnormalitiesmissed on prenatal ultrasound. Methods We reviewed the computerized database of the Division of Cardiology of the Hospital for Sick Children in Toronto to identify all cases of major CHD detected prenatally from 1990 to 2002. Medical records, fetal echocardiograms and ultrasound, cytogenetic and autopsy reports were reviewed. The types of CHD detected were grouped into categories and the frequencies of major extracardiac and chromosomal abnormalities in these categories were noted. Prenatal ultrasound findings were compared with those at autopsy or postnatal examination. Results Of 491 fetuses with major structural CHD, complete data were obtained for 382. Of these, there were 141 (36.9%) with major extracardiac abnormalities at autopsy or postnatal exam, of which 46 had chromosomal abnormalities and 95 did not. In the absence of chromosomal abnormalities, the organ systems most affected were urogenital (12.2%) and gastrointestinal (11.6%). CHDs with the highest incidence of extracardiac abnormalities (>25%) included: heterotaxy, single left ventricle and tricuspid atresia, hypoplastic left heart syndrome and tetralogy of Fallot. Ninety-four of 334 (28.1%) fetuses tested had chromosomal abnormalities. The most common chromosomal abnormalities were trisomies 21 (43.6%), 18 (19.1%) and 13 (9.6%), monosomy X (7.4%) and 22q11.2 deletion (7.4%). Of 289 extracardiac abnormalities from the complete series, 134 (46.4%) were not identified prenatally. Of the missed extracardiac abnormalities, 65 were considered not detectable at prenatal ultrasound, so 23.9% (69/289) of detectable extracardiac abnormalities were missed prenatally. Conclusions Major extracardiac and chromosomal abnormalities are common in fetuses with major fetal CHD. Many important associated extracardiac abnormalities may be missed prenatally, which should be taken into consideration in the prenatal counseling for fetal CHD. © 2009 ISUOG.
Keywords: aortic coarctation; aortic stenosis; aortopulmonary septal defect; arterial trunk; article; atrioventricular septal defect; autopsy; cardiology; chromosome 22q; chromosome aberration; chromosome deletion; comparative study; congenital heart disease; congenital heart malformation; controlled study; counseling; cytogenetics; data base; echocardiography; Fallot tetralogy; fetus; fetus echography; gastrointestinal tract; great vessels transposition; heart disease; heart left ventricle failure; heart right ventricle double outlet; heterotaxy syndrome; hospital; human; hypoplastic left heart syndrome; lung vein drainage anomaly; major clinical study; medical record review; monosomy X; morbidity; perinatal period; prenatal diagnosis; prenatal period; priority journal; pulmonary valve atresia; pulmonary valve stenosis; quality of life; tricuspid valve atresia; tricuspid valve dysplasia; trisomy 13; trisomy 18; trisomy 21; ultrasound; United States; urogenital system; uterus; vascular ring

Challenges and Progress of the Pediatric Cardiac Surgery in Shanghai Children's Medical Center: A 25-year Solid Collaboration With Project HOPE - Liu, J. (Seminars in Thoracic and Cardiovascular Surgery: Pediatric Cardiac Surgery Annual, 2009)
Congenital heart disease (CHD) is one of major categories of illness that, if treated, can restore health and improve quality of life. Unfortunately, in many developing countries, health professionals may not have the resources to replenish themselves with modern technology and/or surgery skills to treat a child with complex CHD. Until now, CHD remained a health challenge for many children and families. During the past few decades, due to limited medical resources and operative techniques, only a very small proportion of the children with CHD in our region were able to be operated for lesion repair. However, the situation in the last 20 years has changed dramatically. Treatment for pediatric CHDs has been greatly improved and developed in China. The collaboration with Project HOPE, an international health professional education organization, has promoted the development of our specialty. Specifically, Project HOPE has played an important role in facilitating the collaboration between Shangahi Xin Hua Hospital, Shanghai Children's Medical Center, and many world-leading pediatric health care institutions. With contributions from Project HOPE in the last 25 years, cardiovascular surgeons at Shanghai Children's Medical Center have achieved tremendous progress. The landmark of the cardiac center and successful clinical data in treating children with cardiac illness symbolizes the successful collaboration among a state-owned hospital, a non-profit organization-Project HOPE, and multiple international corporations, which have provided valuable resources to facilitate the growth of the hospital into a state-of-the-art tertiary hospital to serve children and families. © 2009 Elsevier Inc. All rights reserved.
Keywords: article; Blalock Taussig shunt; child health care; China; clinical competence; congenital heart disease; endocardial cushion defect; Fontan procedure; Glenn shunt; great vessels transposition; health practitioner; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; heart surgery; heart ventricle septum defect; human; international cooperation; medical education; patent ductus arteriosus; pediatric hospital; pediatric surgery; surgical technique

Invited Review: Nutrition support after neonatal cardiac surgery - Owens, J.L.; Musa, N. (Nutrition in Clinical Practice, 2009)
Congenital heart disease is the most common birth defect in the United States, with an estimated frequency of approximately 12ĝ€"14 of 1000 live births per year. Neonates with congenital heart disease often need palliative or corrective surgery requiring cardiopulmonary bypass during the first weeks of life. The neonate undergoing cardiopulmonary bypass surgery experiences a more profound metabolic response to stress than that seen in older children and adults undergoing surgery. However, compared with older children and adults, the neonate has less metabolic reserves and is extremely vulnerable to the negative metabolic impact induced by stress, which can lead to suboptimal wound healing and growth failure. There are complications associated with the metabolic derangements of neonatal surgery requiring cardiopulmonary bypass, including but not limited to acute renal failure, chylothorax, and neurological dysfunction. This article discusses the importance of nutrition and metabolic support for the neonate undergoing cardiopulmonary bypass and the immediate postoperative nutrition needs of such a patient. Also, this article uses a case study to examine the feeding methodology used at one particular institution after neonatal cardiac surgery. The purpose of the case study is to provide an illustration of the many factors and obstacles that clinicians often face in the provision and timing of nutrition support. © 2009 American Society for Parenteral and Enteral Nutrition.
Keywords: amino acid; carbohydrate; fat; lipid; protein; acute kidney failure; article; body composition; body weight; cardiopulmonary bypass; child nutrition; chylothorax; congenital heart disease; energy expenditure; enteric feeding; food composition; growth disorder; human; hypoplastic left heart syndrome; intravenous feeding; metabolic stress; neurologic disease; newborn; newborn surgery; nutritional support; parenteral nutrition; postoperative care; wound healing impairment

Quality-of-life concerns differ among patients, parents, and medical providers in children and adolescents with congenital and acquired heart disease - Marino, B.S.; Tomlinson, R.S.; Drotar, D.; Claybon, E.S.; Aguirre, A.; Ittenbach, R.; Welkom, J.S.; Helfaer, M.A.; Wernovsky, G.; Shea, J.A. (Pediatrics, 2009)
OBJECTIVES. Mortality rates in pediatric patients with heart disease have decreased dramatically in recent decades, resulting in an increasing number of survivors with morbidities that impact quality of life. The purpose of this study was to assess and compare how heart disease affects the quality of life of the pediatric cardiac patient from the perspectives of the patient, parent, and health care provider. METHOD. Individual focus groups were conducted with children (8-12 years of age) with heart disease, adolescents (13-18 years of age) with heart disease, parents of children with heart disease, parents of adolescents with heart disease, and health care providers of pediatric patients with heart disease. A structured focus group technique was used to develop a list of potential items that might affect quality of life. Participants chose the 5 most important items from the list. These items were then categorized into preidentified dimensions (physical, psychological, social, school, and other). The percentages of the total votes for all items were calculated and distributions of responses across dimensions within group and within dimension across groups were reported and compared qualitatively. RESULTS. Patient and parent groups identified similar items as important. Providers identified different items. The physical limitation item received the largest percentage of total votes in all groups (9%-20%). Analysis across dimension revealed that those items related to the physical dimension received the highest percentage of total votes among all groups (30.2%-51.2%). Analysis within dimension revealed that patients endorsed items in the physical dimension more frequently than parents or providers. Within the psychological dimension, the children selected the fewest items relative to all other groups (7.2% vs 21.3%-37.8%), whereas health care providers endorsed these items more frequently than patients or parents (child or parent of child groups 7.2%-21.3% vs health care provider group 28.8%; adolescent or parent of adolescent groups 29.6% vs health care provider group 37.8%). Differences were noted between the child and adolescent groups in the psychological (child versus adolescent: 7.2% vs 29.6%) and school (child versus adolescent: 11.2% vs 2.1%) dimensions. CONCLUSIONS. Patients and parents generally agreed on how heart disease affects the quality of life of children and adolescents, whereas health care providers had a different opinion. Copyright © 2009 by the American Academy of Pediatrics.
Keywords: adolescent; aortic coarctation; aortic stenosis; aortic regurgitation; arterial trunk; article; calculation; cardiac patient; cardiomyopathy; child; complete heart block; congenital heart disease; congestive cardiomyopathy; Fallot tetralogy; female; health care personnel; heart arrhythmia; heart atrium septum defect; heart right ventricle double outlet; heart ventricle septum defect; heart ventricle tachycardia; human; hypoplastic left heart syndrome; information processing; major clinical study; male; mitral valve regurgitation; pediatrics; priority journal; psychological aspect; pulmonary valve atresia; pulmonary valve stenosis; qualitative analysis; quality of life; school child; social aspect; supraventricular tachycardia; tricuspid valve atresia

Fontan patient with plastic bronchitis treated successfully using aerosolized tissue plasminogen activator: A case report and review of the literature - Do, T.B.; Chu, J.M.; Berdjis, F.; Anas, N.G. (Pediatric Cardiology, 2009)
Plastic bronchitis is an uncommon condition characterized by the production of large pale bronchial casts that obstruct the tracheobronchial tree. The cellular content, cohesiveness, and often rubber-like consistency distinguish bronchial casts from the usual mucus plugs found with such disease states as asthma. Plastic bronchitis can be found secondary to many conditions, and a simplified classification scheme organizes it into two groups: an inflammatory type consisting of casts with an eosinophilic inflammatory infiltrate and an acellular type with a predominance of fibrin distinguished by its relative lack of cellular infiltrate, its mucin predominance, and its appearance only in children with congenital cyanotic heart disease. This report describes a 5-year-old girl who experienced plastic bronchitis 3 months after a Fontan procedure for hypoplastic left heart syndrome that was treated successfully with aerosolized tissue plasminogen activator. © 2008 Springer Science+Business Media, LLC.
Keywords: acetylsalicylic acid; albumin; bosentan; dopamine; fibrin; furosemide; milrinone; mucin; salbutamol; spironolactone; tissue plasminogen activator; absence of side effects; article; artificial ventilation; bronchitis; cardiopulmonary insufficiency; case report; child; chylothorax; coughing; croupous bronchitis; disease duration; disease severity; diuresis; dyspnea; endotracheal intubation; eosinophilia; face edema; female; fenestration; fiberoptic bronchoscopy; Fontan procedure; heart failure; human; hypoplastic left heart syndrome; hypotension; inflammatory infiltrate; intensive care unit; low fat diet; lung compliance; lung edema; mental health; pleura effusion; preschool child; pulmonary artery stenosis; stent; thorax drainage; thorax radiography

Dexmedetomidine sedation for pediatric post-Fontan procedure patients - Tokuhira, N.; Atagi, K.; Shimaoka, H.; Ujiro, A.; Otsuka, Y.; Ramsay, M. (Pediatric Critical Care Medicine, 2009)
Objective: The hemodynamic, respiratory, and sedative effects of dexmedetomidine (DEX) for pediatric patients post-Fontan surgery. Design: Retrospective. Setting: Single institutional intensive care unit. Participants: Fourteen patients undergoing Fontan-type surgery. Result: A retrospective review was conducted on 14 pediatric patients who had undergone a Fontan procedure for congenital heart disease. A vital component of postoperative management of these patients is to prevent an increase in pulmonary vascular resistance (PVR) that may lead to a serious reduction in cardiac output. DEX an alpha-2 adrenergic receptor agonist might offer an advantage over current sedation methods in preventing a rise in PVR. Nine patients received sedation with DEX and five patients in a control group were administered standard regimens of sedation and analgesia. The DEX group exhibited no evidence of an increased partial pressure of arterial carbon dioxide postoperatively as opposed to the control group. This lack of respiratory depression made the DEX group less likely to increase their PVR. However, the DEX group did experience a significant incidence of bradycardia that required the use of a cardiac pacemaker. Conclusions: The results of this retrospective review of the role of DEX in the management of the post-Fontan surgical pediatric patient indicate some potential advantages. © 2009 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: dexmedetomidine; propofol; arterial carbon dioxide tension; article; artificial heart pacemaker; bradycardia; child; clinical article; congenital heart malformation; controlled study; drug efficacy; female; Fontan procedure; heart output; hemodynamics; hospitalized child; human; intensive care unit; lung vascular resistance; male; medical record review; pediatric anesthesia; postoperative analgesia; postoperative pain; postoperative period; preschool child; priority journal; respiration depression; retrospective study; school child; sedation; treatment outcome

Feeding abilities in neonates with congenital heart disease: A retrospective study - Jadcherla, S.R.; Vijayapal, A.S.; Leuthner, S. (Journal of Perinatology, 2009)
Objective: An important area concerning morbidity among infants with congenital heart defects (CHD) is related to feeding problems. Our objectives were to characterize the evolution of feeding milestones related to transition to per oral feeding among infants with CHD, and to identify associated variables impacting the feeding abilities. Specifically, we differentiated the feeding characteristics in neonates with acyanotic vs cyanotic CHD. Study Design: Feeding progress was tracked during the first hospitalization in a retrospective chart review study involving 76 infants (29 acyanotic, 47 cyanotic CHD). The ages at which the following milestones attained were recorded: first feeds, maximum gavage feeds, first nipple feeds and maximum nipple feeds, in addition to the length of hospital stay. Effects of perinatal factors, duration of respiratory support, vasopressor and narcotic use and use of cardiopulmonary bypass on the feeding milestones were also evaluated. ANOVA, t-test, and stepwise linear regression analysis were applied as appropriate. Data stated as mean±s.e.m., or %; P<0.05 was considered significant. Result: Prenatal and birth characteristics were similar (P=NS) between the neonates with acyanotic and cyanotic CHD. Cyanotic CHD required three times prolonged use of ventilation, narcotics and vasopressor use (all P<0.05, compared to the acyanotic group). In the acyanotic group, prolonged respiratory support correlated linearly with time to attain maximal gavage feeds and nippling (both, R2=0.8). In the cyanotic group, delayed initiation of gavage feeds and prolonged respiratory support both correlated linearly with time to attain maximal gavage feeds and nippling (both, R2=0.8). Age at first gavage feed correlated with maximum gavage feeds among neonates with cyanotic CHD, and first nipple feed correlated with maximum nipple feeds among all groups (P<0.01). Use of cardiopulmonary bypass in cyanotic CHD delayed the feeding milestones and prolonged the length of stay (both, P<0.05 vs non-bypass group); similar findings were not seen in the acyanotic group. Conclusion: In contrast to neonates with acyanotic CHD, cyanotic CHD group had significant delays with (a) feeding readiness, (b) successful gastric feeding, (c) oromotor readiness and (d) successful oromotor skills. Co-morbid factors that may directly influence the delay in feeding milestones include the (a) duration of respiratory support and (b) use of cardiopulmonary bypass. Delays in achieving maximum gavage and maximum nippling may suggest foregut dysmotility and oropharyngeal dysphagia.
Keywords: hypertensive factor; narcotic agent; aortic coarctation; aortic stenosis; aortoplasty; article; assisted ventilation; atrioventricular block; Blalock Taussig shunt; bottle feeding; cardiopulmonary bypass; congenital heart disease; controlled study; cyanosis; drug use; dysphagia; Fallot tetralogy; feeding behavior; great vessels transposition; heart atrium septum defect; hospitalization; human; hypoplastic left heart syndrome; infant feeding; infant nutrition; intestinal dysmotility; length of stay; lung artery banding; lung vein drainage anomaly; major clinical study; medical record review; motor performance; newborn; newborn morbidity; Norwood procedure; treatment duration

Self-estimated physical functioning poorly predicts actual exercise capacity in adolescents and adults with congenital heart disease - Gratz, A.; Hess, J.; Hager, A. (European Heart Journal, 2009)
Aims: The aim of this study is to compare self-reported health-related quality-of-life (HRQoL) with the objective of exercise performance in patients with congenital heart disease (CHD) according to diagnosis. Methods and results: 564 patients (255 females, 14-73 years) with various CHD (62 shunt, 66 left heart obstruction, 33 PS/PR, 47 Ebstein, 96 Fallot, 98 TGA after atrial switch, 38 other TGA, 31 Fontan, 32 palliated/native cyanotic, 61 others) and a group of 53 healthy controls (18 females, 14-57 years) completed a QoL questionnaire (SF-36) and performed a symptom-limited cardiopulmonary exercise test. Despite several limitations at exercise (P = 1.30 × 10-33), patients only reported reductions in HRQoL concerning physical functioning (P = 4.41 × 10-15) and general health (P = 6.17 × 10-5) and not psychosocial aspects. This could be confirmed in all diagnostic subgroups. Correlation to peak oxygen uptake was found in physical functioning (r = 0.435, P = 1.72 × 10-27) and general health (r = 0.275, P = 3.79 × 10-11). However, there was severe overestimation of physical functioning in most patients when compared with actual exercise test results. Conclusion: Patients with CHD rate their HRQoL impaired only in physical functioning and general health and not in any psychosocial aspect. Self-estimated physical functioning poorly predicts actual exercise capacity. © The Author 2008.
Keywords: adolescent; adult; aerobic exercise; aged; aortic coarctation; aortic stenosis; article; cardiopulmonary exercise test; congenital heart disease; controlled study; cyanotic heart disease; diagnosis related group; Ebstein anomaly; Fallot tetralogy; female; fitness; great vessels transposition; health survey; heart septum defect; human; major clinical study; male; motor performance; oxygen consumption; priority journal; pulmonary valve insufficiency; pulmonary valve stenosis; quality of life; self report; social psychology

Non-invasive positive pressure ventilation for bilateral diaphragm paralysis after pediatric cardiac surgery - Kovacikova, L.; Dobos, D.; Zahorec, M. (Interactive Cardiovascular and Thoracic Surgery, 2009)
We present the case histories of two children having respiratory failure due to bilateral diaphragm paralysis after cardiac surgery. In both children non-invasive positive pressure ventilation alleviated respiratory distress, improved gas exchange, and prevented the need for endotracheal intubation. Following unilateral recovery of diaphragmatic function both children were successfully weaned from non-invasive positive pressure ventilation. © 2009 Published by European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: article; artificial ventilation; Blalock Taussig shunt; breathing rate; case report; child; chylothorax; diaphragm paralysis; endotracheal intubation; Fontan procedure; Glenn shunt; heart atrioventricular node; heart septum defect; heart surgery; human; infant; lung artery banding; lung gas exchange; male; non invasive procedure; parenteral nutrition; peak inspiratory flow; positive pressure ventilation; postoperative complication; preschool child; priority journal; respiratory distress; respiratory failure; respiratory tract infection; ventilator; Servo-i

Living with complex congenital heart disease - Human, D.G. (Paediatrics and Child Health, 2009)
A child with complex congenital heart disease in 2008 is very likely to survive a series of surgical and medical interventions, and confront an array of medical and psychosocial stressors that are presently poorly understood. As approaches to medical problems change, careful assessment of those results is essential, and the initial work of the multicentre Pediatric Heart Network is a huge step in the right direction, setting the stage for proper controlled trials of therapies. Major complications, notably ventricular failure, rhythm problems and thromboembolism, will affect nearly one-quarter of survivors, necessitating further interventions. Appropriate educational and psychosocial support for these children and their families is the next challenge for all of us in the field of paediatrics. How ironic would it be to have invested so much in early survival, only to allow the child to fail in life itself. © 2009 Pulsus Group Inc. All rights reserved.
Keywords: article; body growth; career planning; child growth; clinical feature; cognition; congenital heart disease; exercise tolerance; Fontan procedure; health status; heart rhythm; heart single ventricle; heart ventricle function; human; quality of life; surgical approach; surgical risk; survival rate; survival time; thromboembolism; valvular heart disease

Functional health status of adolescents after the Fontan procedure - Comparison with their siblings - Manlhiot, C.; Knezevich, S.; Radojewski, E.; Cullen-Dean, G.; Williams, W.G.; McCrindle, B.W. (Canadian Journal of Cardiology, 2009)
Background: Studies have suggested that patients who have undergone the Fontan procedure experience lower functional health status and diminished exercise capacity compared with other children. Objectives: To compare the functional health status of Fontan patients with and without siblings, assess whether there are any differences between Fontan patients and their siblings, and determine associated factors. Methods: A cross-sectional, single-centre, observational study was performed on Fontan patients 10 to 20 years of age, and their sibling closest in age, followed in a tertiary pediatric hospital. Functional health status was measured by the Child Health Questionnaire Child Form and the Pediatric Quality of Life, Inventory. Results: A total of 68 patients and 38 siblings were enrolled. Patients with siblings scored significantly lower on numerous domains of physical functional status than those without siblings. Compared with their matched siblings, Fontan patients reported significantly lower scores in all domains of the Pediatric Quality of Life Inventory and on physical (but not psychosocial) domains of the Child Health Questionnaire Child Form. Factors associated with increased patient-sibling differences included younger patient age, female sex, intracardiac lateral tunnel Fontan connection and lower ejection fraction at the time of study enrollment. Conclusions: Adolescents with Fontan physiology reported a lower functional health status in physical domains than their siblings, but had similar status in psychosocial domains. Having a sibling was associated with lower reported functional health status, suggesting an important effect of self-perceived physical limitations over true limitations. © 2009 Pulsus Group Inc. All rights reserved.
Keywords: adolescent; article; Child Health Questionnaire Child Form; controlled study; differentiation; exercise; female; Fontan procedure; functional assessment; health status; heart ejection fraction; human; major clinical study; male; patient sibling difference; PedsQL questionnaire; physical capacity; questionnaire; scoring system; sex difference; sibling

A large teratoma of the hard palate: a case report - Benson, R.E.; Fabbroni, G.; Russell, J.L. (British Journal of Oral and Maxillofacial Surgery, 2009)
Congenital teratoma is a rare malformation, and few papers have been published about it. We present a large teratoma that arose from the hard palate in a neonate. The obstructive mass caused maternal polyhydramnios and was identified prenatally by ultrasonography. The mother went into labour at 35 week's gestation at home. The child was in respiratory distress as a result of airway obstruction, and a tracheostomy was done when she was 4 hours old. She also had major cardiac abnormalities. The palatal mass was removed successfully at 4 weeks of age. The typical components of a teratoma were identified including immature neural glial tissue. © 2008 The British Association of Oral and Maxillofacial Surgeons.
Keywords: airway obstruction; airway pressure; article; cardiovascular malformation; case report; computer assisted tomography; female; fetus echography; gastrotomy; gestational age; glia; hard palate; heart single ventricle; histopathology; human; human tissue; hydramnios; infant; lung ventilation; mouth tumor; newborn; nuclear magnetic resonance imaging; patent ductus arteriosus; physical examination; postoperative care; respiratory distress; spontaneous placental delivery; teratoma; tracheostomy

Transcatheter closure of fenestration after modified fontan operation in children - Meraji, S.M.; Davari, P.N.; Aarabi, M.Y.; Shahmohammadi, A.A.; Mortezaeian, H.; Emamzadegan, R. (Journal of Tehran University Heart Center, 2008)
Background: Fenestration in the modified Fontan operation allows right-to-left shunting, which reduces the Fontan pathway pressure and improves cardiac output. However, on account of the fact that persistent right-to-left shunting results in cyanosis and paradoxical emboli, fenestration closure is recommended after recovery from the Fontan operation. Methods: This study recruited 3 patients who underwent the transcatheter closure of the Fontan fenestration with the ASD-Amplatzer because of severe cyanosis and significant intracardiac shunts. Results: Fenestration closure was performed at a mean age of 8 yr (6-12 yr) and average of 15 months after the Fontan operation. Aortic O2 saturation increased by an average of 17.6% (9-26%). During more than a two-year period of follow-up (mean: 27 months), two patients had complete occlusion on echocardiography and the other one had a small residual shunt. One of these patients had atrial flutter during the follow-up. Conclusion: The transcatheter closure of the Fontan fenestration is a safe and feasible technique that is effective in elevating systemic O2 saturation and well-being and confers acceptable growth and development in children.
Keywords: oxygen; aorta; arterial oxygen saturation; article; case report; catheter; child; clinical effectiveness; cyanosis; disease severity; female; fenestration; follow up; Fontan procedure; great vessels transposition; heart atrium flutter; heart catheterization; heart right ventricle double outlet; heart septum defect; heart single ventricle; heart ventricle septum defect; human; male; patient safety; pulmonary valve stenosis; transthoracic echocardiography; tricuspid valve atresia; ASD-Amplatzer

Routine clinical cardiovascular magnetic resonance in paediatric and adult congenital heart disease: Patients, protocols, questions asked and contributions made - Fratz, S.; Hess, J.; Schuhbaeck, A.; Buchner, C.; Hendrich, E.; Martinoff, S. (Journal of Cardiovascular Magnetic Resonance, 2008)
Background: Cardiovascular Magnetic Resonance (CMR) of patients with congenital heart disease (CHD) has become routine clinical practice. However, existing CMR protocols focus predominantly on patients with ischemic heart disease, and information is limited on the types of patient with CHD who benefit from CMR investigation, and in what ways. Therefore the aim of this study was to answer the questions: What type of patients were studied by CMR in a centre specializing in paediatric and adult CHD management? What questions were asked, which protocols were used and were the questions successfully answered? To answer these questions, we conducted a cohort study of all 362 patients that received routine clinical CMR during 2007 at the Department of Paediatric Cardiology and Congenital Heart Disease at the Deutsches Herzzentrum München. Results: Underlying diagnosis was in 33% Fallot's tetralogy, 17% aortic coarctation, 8% Ebstein's disease, 6% Marfan's disease, 4% single ventricle with Fontan-like circulation, and 32% others. Median age was 26 years (7 days - 75 years). Ventricular volumes were assessed in 67% of the patients; flow in 74%; unknown anatomy only in 9%; specific individual morphology of known anatomy in 83%; myocardial fibrosis in 8%; stress-induced myocardial perfusion defects in 1%. Only in 3% of the cases the question could not be fully answered. Conclusion: Contrary to common belief, routine CMR of patients with CHD was not requested to address global anatomical questions so much as to clarify specific questions of morphology and function of known anatomy. The CMR protocols used differed markedly from those widely used in patients with ischemic heart disease. © 2008 Fratz et al; licensee BioMed Central Ltd.
Keywords: adolescent; adult; adult disease; aged; aortic coarctation; article; child; childhood disease; congenital heart disease; Ebstein anomaly; Fallot tetralogy; heart muscle fibrosis; heart muscle perfusion; heart single ventricle; heart ventricle volume; human; infant; major clinical study; Marfan syndrome; morphology; newborn; nuclear magnetic resonance imaging; practice guideline; preschool child; priority journal; school child

Pulmonary artery size and function after fontan operation at a young age - Robbers-Visser, D.; Helderman, F.; Strengers, J.L.; Van Osch-Gevers, L.; Kapusta, L.; Pattynama, P.M.; Bogers, A.J.; Krams, R.; Helbing, W.A. (Journal of Magnetic Resonance Imaging, 2008)
Purpose: To assess pulmonary artery (PA) size, flow variables, and wall shear stress (WSS) in patients after Fontan operation at a young age. Materials and Methods: Flow in the branch PA was obtained with phase contrast velocity-encoded cardiovascular magnetic resonance imaging in 14 patients before and after low-dose dobutamine stress (7.5 μg/kg/min) and in 17 healthy controls at rest. Results: At rest, stroke index, total flow, average, and peak flow rate were all statistically significantly lower in patients than in controls (P < 0.001). With stress-testing, all variables increased in patients (P < 0.001), apart from stroke index, which did not change. At rest, branch PA area did not differ between patients and controls. Distensibility was lower in patients than in controls (P < 0.001). With stress-testing, area and distensibility did not change. At rest, WSS was lower in patients than in controls (P < 0.001). WSS increased with stress-testing (P < 0.001), but not to the same levels as during resting conditions of the control group. Conclusion: PA size is normal long-term after Fontan operation at a young age. Flow variables, distensibility, and WSS are significantly lower compared to healthy controls, and do not show adequate reactions with stress-testing, which is suggestive of pulmonary artery endothelial and/or vascular dysfunction. © 2008 Wiley-Liss, Inc.
Keywords: adolescent; adult; artery blood flow; artery compliance; artery diameter; article; child; clinical article; contrast enhancement; controlled study; female; Fontan procedure; heart stroke volume; human; male; priority journal; pulmonary artery; shear stress; whole body MRI

Congenital heart disease in children with Down's syndrome: Turkish experience of 13 years - Nisli, K.; Oner, N.; Candan, S.; Kayserili, H.; Tansel, T.; Tireli, E.; Karaman, B.; Omeroglu, R.E.; Dindar, A.; Aydogan, U.; Basaran, S.; Ertugrul, T. (Acta Cardiologica, 2008)
Background - Down's syndrome (DS) is the most common chromosomal abnormality due to a trisomy of chromosome 21 commonly associated with congenital heart defects (CHDs). This study aimed to evaluate the frequency and types of CHD patterns in Turkish children with DS. Method - The data relate to paediatric patients with DS who underwent cardiologic screening between 1994 and 2007 and were reviewed in our Paediatric Cardiology unit. Results - Four hundred and twenty-one out of the 1042 paediatric patients with DS studied over a 13-year period had associated CHD. Of these, 320 (77.6%) had a single cardiac lesion, while the remaining 92 patients (22.4%) had multiple defects. The most common single defect was an atrio-ventricular septal defect (AVSD) found in 141 patients (34.2%), followed by 69 patients (16.7%) showing secundum type atrial septal defect, and ventricular septal defect in 68 patients (16.5%). AVSDs were the leading type, isolated or combined with other cardiac anomalies with an overall occurrence of 19.8% of paediatric patients with DS, and 49.2% of paediatric patients with both DS and CHD. Conclusion - This is the first study concerning the frequency and type of CHD observed in Turkish children with DS. The high frequency of AVSD in Turkish children with DS implied that early screening for CHDs by echocardiography is crucial. The correction of AVSDs in paediatric patients with DS should be performed in the first 6 months of life to avoid irreversible haemodynamic consequences of the defect.
Keywords: adolescent; amniocentesis; aortic valve stenosis; article; cardiovascular surgery; child; chorion villus sampling; comorbidity; congenital heart disease; controlled study; Doppler echocardiography; Down syndrome; Fallot tetralogy; female; fetus blood sampling; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart ventricle septum defect; human; hypoplastic left heart syndrome; infant; major clinical study; male; medical record review; prenatal diagnosis; pulmonary valve stenosis; superior cava vein syndrome; Turkey (republic); two dimensional echocardiography; Vivid 3

Hybrid procedures can reduce the risk of congenital cardiovascular surgery - Schmitz, C.; Esmailzadeh, B.; Herberg, U.; Lang, N.; Sodian, R.; Kozlik-Feldmann, R.; Welz, A.; Breuer, J. (European Journal of Cardio-thoracic Surgery, 2008)
Background: Minimally invasive operations and percutaneous interventions are well-accepted options in the treatment of congenital heart defects. However, percutaneous interventions may be associated with an increased risk due to limited vascular access or a very tortuous catheter course. In these cases, combining operative and interventional approaches with direct puncture of the heart or the great vessels may facilitate implantation of even large devices. Furthermore, in some situations, cardiopulmonary bypass or circulatory arrest can be omitted when doing a hybrid procedure. Patients: Between January 2000 and April 2007 17 patients were operated in a hybrid fashion. Age ranged from 14 days to 45 years. Operative procedures consisted of implantation of an atrial septal defect occluder via direct puncture of the right atrium (n = 4), closure of a ventricular septal defect via direct puncture of the right ventricle (n = 1), implantation of isthmus stents via the ascending aorta (n = 5), redilation of an isthmus stent (n = 1), redilation of a ductal stent (n = 1), angioplasty of a pulmonary artery stenosis (n = 1), interventional occlusion of an intrahepatic porto-caval shunt (n = 1), stent implantation into the right pulmonary artery (n = 1) and into the right ventricular outflow tract (n = 1) under direct vision as well as atrioseptoplasty combined with a bilateral pulmonary artery banding in one newborn with a single ventricle and very low birth weight (n = 1). Results: The planned intervention could be performed in all cases under the assistance of intraoperative fluoroscopy, transesophageal or epicardial echocardiography, or under direct vision. In all cases, the primary hemodynamic objectives were achieved. Conclusion: In selected patients, the combination of a surgical procedure and a percutaneous intervention may help to reduce both operative and interventional risks. This concept may enable new treatment options, especially in patients with complex congenital heart defects or complex vascular situations. © 2008 European Association for Cardio-Thoracic Surgery.
Keywords: heparin; adolescent; adult; angiography; angioplasty; aortic coarctation; article; ascending aorta; Blalock Taussig shunt; cardiovascular surgery; child; clinical article; congenital heart malformation; echocardiography; endoprosthesis; Fallot tetralogy; fluoroscopy; Glenn shunt; heart atrium septum defect; heart right atrium; heart right ventricle; heart right ventricle outflow tract; heart single ventricle; heart ventricle septum defect; hemodynamics; human; hybrid congenital cardiovascular surgery; implantation; infant; low birth weight; lung artery banding; newborn; newborn surgery; patent foramen ovale; portocaval shunt; priority journal; pulmonary artery stenosis; retrospective study; risk reduction; stent; surgical technique; transesophageal echocardiography; treatment indication; treatment outcome; Amplatzer; CP-stent 8Z16

Two-year survival and mental and psychomotor outcomes after the Norwood procedure: An analysis of the modified Blalock-Taussig shunt and right ventricle-to-pulmonary artery shunt surgical eras - Atallah, J.; Dinu, I.A.; Joffe, A.R.; Robertson, C.M.T.; Sauve, R.S.; Dyck, J.D.; Ross, D.B.; Rebeyka, I.M. (Circulation, 2008)
Background - The Norwood procedure for stage 1 palliation of hypoplastic left heart syndrome is performed with either the modified Blalock-Taussig (MBTS) or the right ventricle-to-pulmonary artery (RVPA) shunt. In our institution, surgical practice changed from use of the MBTS to use of the RVPA shunt in 2002. We analyzed survival and mental and psychomotor outcomes of the 2 consecutive surgical eras. Methods and Results - Between September 1996 and July 2005, 94 neonates with hypoplastic left heart syndrome underwent the Norwood procedure. Patients were recruited as neonates and followed up prospectively. Health, mental, and psychomotor outcomes (Bayley Scales of Infant Development-II) were assessed at 2 years. The study subjects were from the Norwood-MBTS era (n=62; 1996 to 2002) or the Norwood-RVPA era (n=32; 2002 to 2005). In the MBTS era, early and 2-year mortality rates were 23% (14/62) and 52% (32/62); the mean (SD) mental and psychomotor developmental indices were 79 (18) and 67 (19). In the RVPA era, early and 2-year mortality rates were 6% (2/32) and 19% (6/32); the mean (SD) mental and psychomotor developmental indices were 85 (18) and 78 (18). The 2-year mortality rate (P=0.002) and the psychomotor developmental index (P=0.029) were improved in the more recent surgical era. On multivariable Cox regression analysis, postoperative highest serum lactate independently predicted 2-year mortality in the MBTS and RVPA eras. Conclusions - Analysis of 2 consecutive surgical eras of hypoplastic left heart syndrome patients undergoing the Norwood procedure showed a significant improvement in 2-year survival and psychomotor development in the more recent era. Adverse neurodevelopmental outcome in this patient population remains a concern. © 2008 American Heart Association. All rights reserved.
Keywords: lactic acid; article; Blalock Taussig shunt; child; clinical trial; controlled clinical trial; controlled study; female; follow up; human; hypoplastic left heart syndrome; lactate blood level; major clinical study; male; mental development; mental function; mortality; nerve cell differentiation; Norwood procedure; outcome assessment; predictive validity; preschool child; priority journal; proportional hazards model; prospective study; psychomotor activity; psychomotor development; right ventricle to pulmonary artery conduit; surgical technique; survival time; treatment outcome

Shock--manifestation of pulmonary atresia with aorto-pulmonary collaterals and single ventricle physiology in a 2-day neonate. - Kovacikova, L.; Skrak, P.; Zahorec, M.; Masura, J. (Bratislavské lekárske listy, 2008)
BACKGROUND: The combination of pulmonary valve atresia and ventricular septal defect accounts for about 2% of cases of congenital heart disease. Most of the cases have intracardiac anatomy of Tetralogy Fallot and present with cyanosis in neonatal age. OBJECTIVES: To report a case of a newborn with rare combination of pulmonary atresia, ventricular septal defect and single ventricle physiology presenting with shock very early following birth. METHODS AND RESULTS: We describe a newborn infant who developed shock with severe metabolic acidosis and respiratory distress several hours following birth. Cardiac ultrasound showed pulmonary atresia and ventricular septal defect with single ventricle physiology. Cardiac cathetrisation revealed major aorto-pulmonary collaterals with an excessive pulmonary blood flow. Resuscitative measures resulted in hemodynamic stability. However, due to unfavorable prognosis, a decision not to undertake surgical palliation was made. Withdrawal of intensive care led to rapid demise of the patient. CONCLUSIONS: We report a case of a newborn with pulmonary atresia, ventricular septal defect and single ventricle physiology in whom an excessive flow through major aorto-pulmonary collaterals led to shock and death very early following birth (Fig. 1, Ref. 5). Full Text (Free, PDF) www.bmj.sk.
Keywords: article; case report; collateral circulation; congenital malformation; heart septum defect; heart ventricle; human; lung; male; newborn; pulmonary valve atresia; shock; vascularization

In-training examination and the general pediatric certification examination: Are there lessons? - Long, S.S. (Journal of Pediatrics, 2008)
Keywords: diphtheria pertussis tetanus vaccine; minocycline; article; attention deficit disorder; autoimmunity; brain disease; certification; child health care; cystic fibrosis; developmental psychology; Down syndrome; esophagus atresia; esophagus fistula; human; hypoplastic left heart syndrome; necrotizing enterocolitis; newborn screening; Norovirus; pediatrics; prematurity; priority journal; smoking

Maternal global methylation status and risk of congenital heart diseases - Steegers-Theunissen, R.P.M.; Van Driel, L.M.J.W.; De Jonge, R.; Helbing, W.A.; Van Zelst, B.D.; Ottenkamp, J.; Steegers, E.A.P. (Obstetrics and Gynecology, 2008)
OBJECTIVE: To investigate whether the association between the maternal methylation status as reflected by low S-adenosylmethionine and high S-adenosylhomocysteine, is detrimental for cardiogenesis and congenital heart disease (CHD) in the offspring. METHODS: As part of a case-control study in the western part of the Netherlands, we evaluated 231 mothers of children with CHD and 315 control mothers of nonmalformed children. The total case group was analyzed and stratified into isolated (n=180) and nonisolated CHDs (n=51). The latter subgroup was further subdivided into Nonsyndromic (n=20), Down Syndrome (n=19), and Other Syndromes (n=12). A multivariable general linear model was used to test for differences between the case groups and controls. All analyses were adjusted for current B vitamin supplement use. RESULTS: Plasma total homocysteine was significantly different between the total case group (median, range 10.3, 4.0-43.8, P=.026) and the nonisolated cases (11.1, 5.5-43.8, P=.006) compared with the controls (10.0, 5.3-42.0). The subgroup of Down Syndrome presented significantly higher total homocysteine and S-adenosylhomocysteine levels and a lower S-adenosylmethionine/S-adenosylhomocysteine ratio than controls. CONCLUSION: Maternal hyperhomocysteinemia, and not hypomethylation, is a risk factor for having a child with CHD. Maternal hypomethylation, however, seems to be associated with offspring having CHD and Down syndrome. © 2008 by The American College of Obstetricians and Gynecologists.
Keywords: biological marker; homocysteine; s adenosylhomocysteine; ademetionine; vitamin B group; adult; aortic coarctation; aortic valve stenosis; article; cardiovascular risk; case control study; child; congenital heart disease; control group; controlled study; Down syndrome; evaluation study; Fallot tetralogy; female; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; human; hyperhomocysteinemia; hypoplastic left heart syndrome; major clinical study; methylation; mother; Netherlands; priority journal; progeny; pulmonary valve stenosis; risk factor; stratification; vitamin supplementation

Congenital heart defects in patients with oculo-auriculo-vertebral spectrum (Goldenhar syndrome) - Digilio, M.C.; Calzolari, F.; Capolino, R.; Toscano, A.; Sarkozy, A.; De Zorzi, A.; Dallapiccola, B.; Marino, B. (American Journal of Medical Genetics, Part A, 2008)
The oculo-auriculo-vertebral spectrum (OAVS) is a non-random association of microtia, hemifacial microsomia with mandibular hypoplasia, ocular epibulbar dermoid, and cervical vertebral malformations. Congenital heart defects (CHDs) have been reported in 5-58% of the patients. We analyze the frequency and anatomic features of CHD in a series of 87 patients with OAVS examined between January 1990 and February 2007 with normal chromosomes, ranging in age between 0.1 and 16.8 years. A twin pregnancy occurred in eight cases (dizygotic in six cases and monozygotic in two). CHDs were diagnosed in 28/87 (32%) patients, and classified into categories of postulated developmental mechanisms including 9 (32%) atrial and ventricular septal defects, 11 (39%) conotruncal defects, 4 (14%) targeted growth defects, two (7%) with situs and looping defects, one (4%) with a left-sided obstructive lesion and one (4%) with patent ductus arteriosus. As noted in other series, the most common individual CHDs were ventricular septal defect (six patients) and tetralogy of Fallot (TOF) (classic or with pulmonary atresia) (six patients). Comparing the frequencies of CHDs groups observed in the OAVS patients with the findings of the Emilia-Romagna Registry which ascertained CHDs prevalence in the general population, conotaincal defects, targeted growth defects, and heterotaxia were significantly associated with OAVS. © 2008 Wiley-Liss, Inc.
Keywords: adolescent; aortic coarctation; article; brain malformation; cerebellum hypoplasia; cervical spine; child; cleft lip palate; clinical feature; conduction deafness; congenital heart malformation; conotruncal heart defect; dextrocardia; disease association; dizygotic twins; face malformation; Fallot tetralogy; female; Goldenhar syndrome; heart atrium septum defect; heart left right shunt; heart right ventricle double outlet; heart ventricle septum defect; hemifacial microsomia; heterotaxia; human; hydrocephalus; infant; kidney malformation; lung hypoplasia; lung vein drainage anomaly; major clinical study; male; mandible hypoplasia; mental deficiency; microphthalmia; microtia; monozygotic twins; patent ductus arteriosus; perception deafness; prevalence; priority journal; pulmonary valve atresia; pulmonary valve stenosis; register; scimitar syndrome; skeleton malformation; spine malformation; teratoma; tricuspid valve atresia; twin pregnancy; vertebra malformation

Fontan Fenestration Closure Has No Acute Effect on Exercise Capacity but Improves Ventilatory Response to Exercise - Meadows, J.; Lang, P.; Marx, G.; Rhodes, J. (Journal of the American College of Cardiology, 2008)
Objectives: The aim of this study was to prospectively examine the effects of elective Fontan fenestration closure upon exercise capacity and ventilatory abnormalities. Background: For patients undergoing Fontan procedures as palliation of single ventricle physiology, the addition of a fenestration to the procedure mitigates perioperative morbidity. Although some fenestrations may close spontaneously, many remain patent and subject patients to arterial hypoxemia and risk for paradoxical emboli. For these reasons fenestration closure is routinely performed post-operatively in the cardiac catheterization laboratory. Although closure of Fontan fenestrations typically results in an immediate improvement in systemic arterial oxygen saturation, it is also associated with an acute decrease in cardiac index and systemic O2 delivery. The sum result of these physiologic changes upon exercise capacity has not been examined. Methods: Twenty consecutive patients, age 5 to 46 (median 10) years, underwent pre- and post-fenestration closure exercise testing with expiratory gas analysis. Results: Before fenestration closure, peak oxygen consumption (VO2) was depressed and there was systemic desaturation at rest that worsened with exercise. The ventilatory response to exercise was also abnormal, characterized by elevation of the minute ventilation (VE)/CO2 elimination slope (VE/VCO2), a low end-tidal CO2, and high end-tidal O2 at the ventilatory anaerobic threshold. Although arterial saturation improved significantly after fenestration closure, there was no change in peak VO2 (70.9 ± 18.6% to 74.0 ± 18.6%, p = NS), heart rate, or O2 pulse at peak exercise. In contrast, ventilatory abnormalities (VE/VCO2) improved considerably (44.4 ± 10.9 to 33.3 ± 5.5, p ≤ 0.001). Conclusions: Fontan fenestration closure does not significantly improve peak VO2. However, ventilatory abnormalities improve considerably. © 2008 American College of Cardiology Foundation.
Keywords: carbon dioxide; adolescent; adult; article; cardiovascular risk; child; clinical article; controlled study; exercise; fenestration; Fontan procedure; heart catheterization; heart ventricle failure; human; lung minute volume; morbidity; oxygen consumption; priority journal

64-Slice multidetector-row computed tomographic angiography for evaluating congenital heart disease - Khatri, S.; Varma, S.K.; Khatri, P.; Kumar, R.S. (Pediatric Cardiology, 2008)
This study aimed to assess critically the role of 64-slice multidetector-row computed tomographic (MDCT) angiography for evaluating congenital heart disease. The study enrolled 60 consecutive patients (median age, 4.7 years; median weight, 16.5 kg) with congenital heart disease who underwent 64-slice MDCT angiography during the period June 2006 through September 2007. The results were classified as diagnostic categories, and the impact of the procedure on strategizing management was critically analyzed. In each of the groups, the current technique offered a clear advantage over conventional imaging and provided specific clues for surgical/interventional management. A management algorithm was evolved based on questions frequently asked about pulmonary artery anatomy. The correlation with surgical anatomy in all cases that involved surgery was excellent. Early results suggest that 64-slice MDCT angiography is a major breakthrough in cardiovascular imaging with an important diagnostic and decision-aiding role. Diagnostic cardiac catheterization, especially for evaluating great vessel anomalies, could be largely replaced by the described technique for congenital heart disease. © 2008 Springer Science+Business Media, LLC.
Keywords: adolescent; adult; algorithm; aortopulmonary shunt; article; cardiovascular system; child; clinical decision making; computed tomographic angiography; congenital heart disease; controlled study; diagnostic imaging; diagnostic value; female; Fontan procedure; heart catheterization; human; infant; major clinical study; male; multidetector computed tomography; pulmonary artery; surgical anatomy; Williams Beuren syndrome

A novel constellation of cardiac findings for Kabuki syndrome: Hypoplastic left heart syndrome and partial anomalous pulmonary venous drainage - Shahdadpuri, R.; Lynch, S.A.; Murchan, H.; McMahon, C.J. (Pediatric Cardiology, 2008)
This report describes the case of a child with Kabuki syndrome, hypoplastic left heart syndrome, and right-sided partial anomalous pulmonary venous drainage to the inferior vena cava. The child underwent successful Norwood and Glenn palliative procedures. At the age of 9 months, the genetic condition was recognized. This represents the first report describing this combination of findings for Kabuki syndrome. © 2008 Springer Science+Business Media, LLC.
Keywords: angiocardiography; aortic coarctation; aortic valve stenosis; article; Blalock Taussig shunt; cardiomegaly; case report; developmental disorder; face dysmorphia; genetic analysis; Glenn shunt; growth retardation; heart catheterization; heart right ventricle hypertrophy; human; hypoplastic left heart syndrome; infant; inferior cava vein; Kabuki makeup syndrome; levocardia; lung vein drainage anomaly; mitral valve stenosis; Norwood procedure; patent ductus arteriosus; phenotype; prenatal diagnosis; systolic heart murmur; thorax radiography; transthoracic echocardiography

Outcomes of management decisions by parents for their infants with hypoplastic left heart syndrome born with and without a prenatal diagnosis - Tibballs, J.; Cantwell-Bartl, A. (Journal of Paediatrics and Child Health, 2008)
Aim: To study the influence of a prenatal diagnosis on parental choice of treatment for infants born with hypoplastic left heart syndrome (HLHS). Methods: Retrospective review of medical records of infants admitted to a paediatric tertiary hospital 1983-2004 with a diagnosis of HLHS. Results: A total of 201 infants had HLHS diagnosed by echocardiography after birth with 129 subsequently undergoing surgery and 72 non-surgical management (compassionate/comfort care). When the diagnosis of HLHS was made prenatally, 68 of 71 (96%) infants underwent surgery whereas when the diagnosis was made post-natally 61 of 130 (47%) infants underwent surgery. Prenatal diagnosis was significantly associated with a parental choice of surgery (P < 0.001). Among 72 infants managed non-surgically, compassionate care was chosen by parents for 49 (68%) despite being fit for surgery, 20 (28%) were deemed unfit for surgery and in three (4%) the reasons for non-surgical management were unknown. Of the total 178 infants considered fit for surgery, 68 (38%) had had a prenatal diagnosis and 110 (62%) did not. Of 20 considered unfit for surgery, none had had a prenatal diagnosis. A prenatal diagnosis was significantly associated with fitness for surgery (P < 0.001). Conclusions: Approximately half of parents chose non-surgical management (compassionate care) of their infant if the diagnosis was post-natal. Although most parents of infants born with a prenatal diagnosis of HLHS chose surgical management of their infant, this is the likely influence of termination of pregnancy for this condition. Lack of prenatal diagnosis compromised fitness for surgery. © 2008 The Authors.
Keywords: article; decision making; heart surgery; human; hypoplastic left heart syndrome; infant; major clinical study; outcome assessment; parental attitude; patient care; prenatal diagnosis; priority journal

Place, age, and mode of death of infants and children with hypoplastic left heart syndrome: Implications for medical counselling, psychological counselling, and palliative care - Cantwell-Bartl, A.M.; Tibballs, J. (Journal of Palliative Care, 2008)
A review of outcomes of hypoplastic left heart syndrome at a pediatric hospital 1983-2004 identified 154 deaths among 206 children (75%). Of 134 surgically treated, 82 (62%) died: 68 (83%) in intensive care, six (7%) in the operating theatre, three (4%) during transport from home, two (2%) on the cardiac ward, one (1 %) at home, one (1 %) in the emergency department, and one (1 %) elsewhere. Seventy died after stage one Norwood surgery (median age: 13 days), three died after second stage surgery (ages: 3, 4, and 20 months), two died after third stage surgery (ages: 1.2 and 3.5 years), two died after heart transplantation (ages: 4.6 and 15 years), and five died after non-Norwood surgery. All 72 infants treated without surgery died: 68 died at a median age 3 days; 57 (79%) in intensive care, three (4%) on the ward, and 12 (17%) elsewhere. Discussion involves strategies to support parents and staff at diagnosis, and before and after a child's death. © 2008 Centre for Bioethics, IRCM.
Keywords: adolescent; age distribution; article; Australia; bereavement; child; counseling; decision making; heart surgery; human; human relation; hypoplastic left heart syndrome; infant; mortality; newborn; parent; preschool child; psychological aspect; retrospective study

HLHS--congenital heart defect in High Risk Pregnancy Unit in 2001-2007. - Karowicz-Bilińska, A.; Berner-Trabska, M.; Kazimierak, W.; Brzozowska, M.; Kowalska-Koprek, U.; Pasiński, J.; Kuś, E. (Ginekologia polska, 2008)
BACKGROUND: HLHS (hypoplastic left heart syndrome) is a serious congenital heart defect. In neonates with congenital heart disease HLHS accounts for nearly 25% of neonatal deaths. The etiology of HLHS is unknown. At present we expect to have those cases diagnosed in the second trimester of pregnancy. AIM: The main aim was to find the rate and outcome of the congenital heart defect--left heart hypoplasia (HLHS). MATERIAL AND METHODS: All cases of this heart defect found in the High Risk Pregnancy Clinic in 2001-2007 were presented. Twice the congenital malformation was diagnosed after delivery and once during pregnancy--in the second trimester. All babies were delivered between 38 and 39 weeks of pregnancy, one by the spontaneous normal delivery, one by elective caesarean section and one by emergency caesarean section because of fetal distress during the delivery. All of the newborns were transported to the Pediatric Cardio surgery Unit of M.U. and operated in first weeks after delivery. RESULTS: In two cases the operation was complicated and children died due to the cardiac arrest. One of the babies died before surgical correction. Two of the women, whose babies died after the operation gave birth to healthy newborns with no cardiac abnormalities. CONCLUSION: The HLHS is the most serious heart congenital malformation diagnosed often after the delivery because of lack of sufficient diagnostic system in healthy women. The prognosis for the children is bad, but the chance of giving birth to healthy children in the future is good.
Keywords: adult; article; differential diagnosis; female; high risk pregnancy; human; hypoplastic left heart syndrome; methodology; Poland; pregnancy; pregnancy outcome; prenatal care; prenatal diagnosis; prognosis; retrospective study; second trimester pregnancy

Usefulness of Cardiac Magnetic Resonance Imaging Combined With Low-Dose Dobutamine Stress to Detect an Abnormal Ventricular Stress Response in Children and Young Adults After Fontan Operation at Young Age - Robbers-Visser, D.; Jan ten Harkel, D.; Kapusta, L.; Strengers, J.L.; Dalinghaus, M.; Meijboom, F.J.; Pattynama, P.M.; Bogers, A.J.; Helbing, W.A. (American Journal of Cardiology, 2008)
After Fontan operation, patients are limited in increasing cardiac output and in exercise capacity. This has been related to impaired preload or other factors leading to decreased global ventricular performance with stress. To study these factors, the stress responses of functionally univentricular hearts were assessed at rest and during low-dose dobutamine stress using cardiovascular magnetic resonance imaging. Thirty-two patients after Fontan completion at young age were included (27 with total cavopulmonary connection, 5 with atriopulmonary connection; mean age 13.3 years, range 7.5 to 22.2; 23 male patients; median follow-up after Fontan operation 8.1 years, range 5.2 to 17.8). A multiphase short-axis stack of 10 to 12 contiguous slices of the systemic ventricle was obtained at rest and during low-dose dobutamine stress cardiovascular magnetic resonance imaging (maximum 7.5 μg/kg/min). With stress-testing, heart rate, ejection fraction, and cardiac index increased adequately (p <0.001). There was an abnormal decrease in end-diastolic volume and an adequate decrease in end-systolic volume (p <0.001). Stroke volume did not change with stress testing (p = 0.15). At rest, dominant left ventricles had higher ejection fractions than dominant right ventricles (p = 0.01), but this difference disappeared with stress testing. In conclusion, a functionally univentricular heart after Fontan completion at young age has an adequate increase in ejection fraction with β-adrenergic stimulation. However, as a result of impaired preload with stress, cardiac output can be increased only by increasing heart rate. © 2008 Elsevier Inc. All rights reserved.
Keywords: dobutamine; adolescent; adrenergic system; adult; article; atriopulmonary connection; blood flow; cavopulmonary connection; child; clinical article; continuous infusion; diagnostic value; exercise test; female; follow up; Fontan procedure; groups by age; heart afterload; heart ejection fraction; cardiac index; heart muscle contractility; heart output; heart preload; heart rate; heart stress; heart ventricle enddiastolic pressure; heart ventricle function; human; low drug dose; male; nuclear magnetic resonance imaging; postoperative complication; priority journal; statistical significance; cerebrovascular accident; venous return

Management of 239 Patients with Hypoplastic Left Heart Syndrome and Related Malformations from 1993 to 2007 - Jacobs, J.P.; O'Brien, S.M.; Chai, P.J.; Morell, V.O.; Lindberg, H.L.; Quintessenza, J.A. (Annals of Thoracic Surgery, 2008)
Background: We reviewed our entire programmatic operative experience with children with hypoplastic left heart syndrome (HLHS) and related malformations. Methods: As of October 1, 2007, 239 patients with HLHS and related malformations underwent surgical treatment at the Congenital Heart Institute of Florida. This manuscript focuses on the 199 initially treated with Norwood stage 1. Results: One hundred and ninety-nine patients were initially treated with Norwood stage 1. Univariate analysis demonstrated the following significant predictors of mortality: right ventricular dominance (p = 0.0023), mechanical circulatory support before stage 1 (p = 0.0192), and significant noncardiac abnormality or syndrome, including Down syndrome, Turner syndrome, heterotaxy, asplenia, polysplenia, biliary atresia, or other chromosomal abnormality (p < 0.0001). Multivariable logistic regression analysis revealed the presence of a significant noncardiac abnormality or syndrome or prematurity less than 35 weeks or mechanical circulatory support before stage 1 to be a significant predictor of mortality (p < 0.0001). Over the 14 years of this patient series, survival for the 157 "low-risk" patients managed with Norwood staged palliation (those patients without significant noncardiac abnormality or syndrome or prematurity less than 35 weeks or mechanical circulatory support prior to Stage 1) was 86%, 80%, and 69% at 30 days after Stage 1, hospital discharge after Stage 1, and 1 year of after Stage 1, respectively. Conclusions: Several treatment options are available for HLHS and related malformations. The appropriate treatment strategy must be matched to the individual patient, taking into consideration anatomic variables as well as other patient-specific characteristics. The majority of patients with HLHS and related malformations can undergo successful staged palliation with risk that varies according to several documented anatomic and patient-specific variables. © 2008 The Society of Thoracic Surgeons.
Keywords: accessory spleen; article; asplenia; assisted circulation; bile duct atresia; chromosome aberration; congenital heart malformation; Down syndrome; heart surgery; heterotaxy syndrome; human; hypoplastic left heart syndrome; priority journal; Turner syndrome; univariate analysis

Feasibility of the extracardiac conduit Fontan procedure in patients weighing less than 10 kilograms - Ikai, A.; Fujimoto, Y.; Hirose, K.; Ota, N.; Tosaka, Y.; Nakata, T.; Ide, Y.; Sakamoto, K. (Journal of Thoracic and Cardiovascular Surgery, 2008)
Objective: The extracardiac conduit Fontan procedure has led to improved outcomes. We performed the procedure in patients weighing less than 10 kg and evaluated its feasibility. Methods: Since January 1999, 72 patients weighing less than 20 kg underwent extracardiac conduit Fontan procedure with polytetrafluoroethylene conduits. The patients were divided into 2 groups: 36 patients weighing less than 10 kg in group S and 36 weighing more than 10 kg in group L. Mean weight, median age, and median follow-up period in groups S and L were 8.5 ± 1.1 and 14.0 ± 3.0 kg, 18.9 and 42.0 months, and 29.2 (1.7-79.7) and 42.1 (2.8-94.2) months, respectively. Postoperatively, most patients received peritoneal drainage catheters. We reviewed data precatheterization and postcatheterization and postoperative course. Results: Conduit sizes in groups S and L were 17.0 ± 1.3 and 17.9 ± 1.9 mm, respectively (P = .03). Five patients required fenestrations. There were 2 hospital deaths, 1 in each group, and 2 late deaths in group S. The postoperative course was identical in both groups, except for median length of stay in the intensive care unit and peritoneal drainage volume. Group S versus L: ventilator support, 11 versus 7 hours; pleural drainage, 9 days each; pleural drainage greater than 14 days, 6 versus 5 cases; peritoneal drainage, 8 versus 7 days; intensive care unit stay, 7 versus 4 days (P = .01), peritoneal drainage volume, 26.1 versus 14.1 mL · kg · d-1 (P = .0007). Conclusions: The early outcome of the extracardiac conduit Fontan procedure was satisfactory in patients weighing less than 10 kg. However, the required size of the conduit remains debatable. © 2008 The American Association for Thoracic Surgery.
Keywords: isoprenaline; polytetrafluoroethylene; abdominal drainage; article; artificial ventilation; body weight; controlled study; feasibility study; fenestration; Fontan procedure; human; intensive care unit; length of stay; major clinical study; patient satisfaction; peritoneal catheter; pleura fluid; postoperative care; preschool child; priority journal; sternotomy; surgical mortality; surgical technique; treatment outcome

Effects of home-based training at dyspnea threshold in children surgically repaired for congenital heart disease - Amiard, V.; Jullien, H.; Nassif, D.; Bach, V.; Maingourd, Y.; Ahmaidi, S. (Congenital Heart Disease, 2008)
The present investigation was aimed at assessing the effect of home-based training on cardiorespiratory responses in children surgically corrected for congenital heart impairment using dyspnea threshold (DT) as training intensity. A group of 23 children aged 15 ± 1.4 years who had undergone surgical correction for congenital heart disease (CHD group) and 12 healthy children used as a control group performed an exercise protocol during which aerobic capacity, ventilatory threshold (VT), and DT were assessed. Afterwards, the CHD group was divided into two subgroups: trained and untrained subjects. Training sessions over a period of 2 months were performed at an intensity corresponding to DT by the CHD trained group. Dyspnea was scored according to a visual analog scale during the warm up, at each exercise stage, and during the recovery period. DT was located on the oxygen uptake/dyspnea curve when a sudden increase in the dyspnea score occured, while VT was defined according to the methodology previously employed by Beaver and colleagues. The results showed that children who had undergone surgery for CHD had reduced aerobic capacity. No significant difference was observed between VT and DT in children corrected for CHD. These two thresholds were highly related. Home-based training at DT did not strongly improve aerobic capacity nor did it influence the relationship between VT and DT. Further studies should be conducted to confirm these preliminary findings, particularly when aerobic capacity is improved by training. © 2008 Copyright the Authors Journal Compilation © 2008 Wiley Periodicals, Inc.
Keywords: anticoagulant agent; carbon dioxide; cardiotonic agent; dipeptidyl carboxypeptidase inhibitor; diuretic agent; immunosuppressive agent; oxygen; adolescent; aerobic capacity; article; bicycle ergometry; cardiopulmonary exercise test; cardiopulmonary function; cardiovascular surgery; clinical article; congenital heart disease; controlled study; dyspnea; exercise; Fallot tetralogy; female; functional training; great vessels transposition; heart atrium septum defect; heart failure; heart single ventricle; home care; human; lung gas exchange; lung minute volume; lung ventilation; male; medical assessment; methodology; oxygen consumption; priority journal; pulmonary valve atresia; pulmonary valve stenosis; scoring system; task performance; treatment outcome; visual analog scale

Effects of transcatheter closure of fontan fenestration on exercise tolerance - Momenah, T.S.; Eltayb, H.; Oakley, R.E.; Qethamy, H.A.; Faraidi, Y.A. (Pediatric Cardiology, 2008)
Baffle fenestration is associated with a significantly better outcome in standard and high-risk patients undergoing completion of Fontan. We report the effects of subsequent transcatheter closure of fenestration on exercise capacity and oxygen saturation. Sixteen patients with a mean age of 10.3 years underwent Amplatzer septal occluder (ASO) device transcatheter closure of Fontan fenestration. All had a fenestrated Fontan operation 6 month to 8 years prior to the procedure. A stress test was performed before and after device closure of fenestration in 14 patients (2 patients did not tolerate stress test before the procedure). The fenestrations in all patients were successfully occluded with the use of the Amplatzer device occluder. No complications occurred during or after the procedure. O2 saturation increased from a mean 85.1 ± 7.89% to 94.5 ± 3.63% (p < 0.01) at rest and from 66.2 ± 12.86% to 87.2 ± 8.64% (p < 0.01) following exercise. Exercise duration has also increased from 8.22 ± 2.74 min to 10.29 ± 1.91 min (p < 0.05). Transcatheter closure of Fontan fenestration increases the duration of exercise capacity and increases O2 saturation at rest and after exercise. © 2007 Springer Science+Business Media, LLC.
Keywords: adolescent; article; artificial embolization; child; devices; exercise; exercise test; exercise tolerance; fenestration; Fontan procedure; heart catheterization; heart right atrium; human; oxygen saturation; surgical technique

The development of the pediatric cardiac quality of life inventory: A quality of life measure for children and adolescents with heart disease - Marino, B.S.; Shera, D.; Wernovsky, G.; Tomlinson, R.S.; Aguirre, A.; Gallagher, M.; Lee, A.; Cho, C.J.; Stern, W.; Davis, L.; Tong, E.; Teitel, D.; et al. (Quality of Life Research, 2008)
Objective: Mortality after surgery for congenital heart disease (CHD) has decreased. Quality of life (QOL) assessment in survivors has become increasingly important. The purpose of this project was to create the Pediatric Cardiac Quality of Life Inventory (PCQLI). Methods: Items were generated through nominal groups of patients, parents, and providers. The pilot PCQLI was completed by children (age 8-12), adolescents (age 13-18), and their parents at three cardiology clinics. Item reduction was performed through analysis of items, principal components, internal consistency (IC), and patterns of correlation. Results: A total of 655 patient-parent pairs completed the pilot PCQLI. Principal components identified included: impact of disease (ID); psychosocial impact (PI); and emotional environment (EE). After item reduction ID and PI had excellent IC (ID = 0.88-0.91; PI = 0.78-0.85) and correlated highly with each other (0.81-0.90) and with the total score (TS) (ID = 0.95-0.96; PI = 0.87-0.93). EE was not correlated with ID, PI, or TS and was removed from the final forms. Two-ventricle CHD patients had a higher TS than single-ventricle CHD patients across all forms (P < 0.001). Conclusion: The PCQLI has patient and parent-proxy forms, has wide age range, and discriminates between CHD subgroups. The ID and PI subscales of the PCQLI have excellent IC and correlate well with each other and the TS. © 2008 Springer Science+Business Media B.V.
Keywords: adolescent; adult; article; child; emotionality; female; heart disease; heart single ventricle; heart ventricle; human; internal consistency; major clinical study; male; pediatric cardiac quality of life inventory; pilot study; principal component analysis; priority journal; psychosocial care; quality of life

Decreased Exercise Performance with Age in Children with Hypoplastic Left Heart Syndrome - Jenkins, P.C.; Chinnock, R.E.; Jenkins, K.J.; Mahle, W.T.; Mulla, N.; Sharkey, A.M.; Flanagan, M.F. (Journal of Pediatrics, 2008)
Objective: Children born with hypoplastic left heart syndrome (HLHS) may experience cardiac dysfunction after staged surgery or transplantation, which may worsen with age. We examined the hypothesis that exercise testing can address cardiovascular capacity and suggest interventions to improve quality of life. Study design: Children with HLHS ≥8 years old performed treadmill or bicycle ergometric testing at 4 centers. Results were compared with norms for age and sex. Results: Of the 42 participants, the mean age was 12.9 years (range, 8.5-17.0 years), 64% were boys, 20 had staged surgery, and 34 completed metabolic assessment. The percent of predicted maximal oxygen uptake (mVO2) was higher in younger children. Children aged 8 to 12 years achieved 70% of predicted mVO2; children aged 13 to 17 years achieved 60% of predicted mVO2 (P = .02). The percent of predicted peak heart rate trended higher in younger patients (83% versus 75%, P = .07). Electrocardiographic changes were more common in older children. In treadmill testing, patients who had a transplant had better exercise performance than patients who underwent staged surgery in percent of predicted exercise time (82% versus 54%, P < .0001) and peak rate-pressure product (241 × 103 versus 195 × 103, P = .02). The percent of predicted mVO2 did not differ between patients who had a transplant (66%) and patients who underwent staged surgery (61%, P = .25). Conclusion: Children with HLHS showed considerable age-related decline in exercise performance, regardless of surgical strategy. © 2008 Mosby, Inc. All rights reserved.
Keywords: adolescent; article; bicycle ergometry; cardiovascular function; child; clinical article; comparative study; controlled study; electrocardiography; exercise test; female; heart disease; heart rate; heart transplantation; human; hypoplastic left heart syndrome; male; oxygen consumption; physical activity; priority journal; quality of life; statistical significance; treadmill exercise; vascular capacity

Maternal smoking and congenital heart defects - Malik, S.; Cleves, M.A.; Honein, M.A.; Romitti, P.A.; Botto, L.D.; Yang, S.; Hobbs, C.A. (Pediatrics, 2008)
OBJECTIVES.In a population-based case-control study, we investigated the association between congenital heart defects and maternal smoking. METHODS.The National Birth Defects Prevention Study enrolled 3067 infants with nonsyndromic congenital heart defects and their parents and 3947 infants without birth defects and their parents. Affected infants had ≥1 of the following defects: conotruncal, septal, anomalous pulmonary venous return, atrioventricular septal defects, and left-sided or right-sided obstructive heart defects. Mothers of case and control infants were asked if they smoked during the periconceptional period, defined as 1 month before pregnancy through the first trimester. Maternal home and workplace exposure to tobacco smoke during the same period was also determined. Logistic regression was used to compute odds ratios and 95% confidence intervals while controlling for potential confounders. RESULTS. Case infants were more likely to be premature and have lower birth weight than control infants. Women who smoked anytime during the month before pregnancy to the end of the first trimester were more likely to have infants with septal heart defects than women who did not smoke during this time period. This association was stronger for mothers who reported heavier smoking during this period. This relation was independent of potential confounding factors, including prenatal vitamin use, alcohol intake, maternal age, and race or ethnicity. Women who smoked ≥25 cigarettes per day were more likely than nonsmoking mothers to have infants with right-sided obstructive defects. There was no increased risk of congenital heart defects with maternal exposure to environmental tobacco smoke. CONCLUSIONS. Maternal smoking during pregnancy was associated with septal and right- sided obstructive defects. Additional investigation into the timing of tobacco exposure and genetic susceptibilities that could modify this risk will provide a more precise evidence base on which to build clinical and public health primary prevention strategies. © 2008 by the American Academy ofPediatrics.
Keywords: tobacco smoke; adult; alcohol consumption; aortic arch interruption; aortic coarctation; article; comparative study; congenital heart malformation; controlled study; disease association; ethnicity; Fallot tetralogy; female; first trimester pregnancy; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; home environment; human; hypoplastic left heart syndrome; infant; low birth weight; major clinical study; male; maternal age; maternal care; maternal smoking; patent ductus arteriosus; population based case control study; prematurity; prenatal exposure; priority journal; pulmonary valve stenosis; pulmonary vein malformation; tricuspid valve atresia; venous return; vitamin supplementation; workplace

Feeding difficulties and growth delay in children with hypoplastic left heart syndrome versus d-transposition of the great arteries - Davis, D.; Davis, S.; Cotman, K.; Worley, S.; Londrico, D.; Kenny, D.; Harrison, A.M. (Pediatric Cardiology, 2008)
The objective of this study was to identify the incidence of feeding difficulties in infants with hypoplastic left heart syndrome (HLHS) and d-transposition of the great arteries (d-TGA). Congenital heart disease is a risk factor for growth failure. The etiologies include poor caloric intake, inability to utilize calories effectively, and increased metabolic demands. The goals of our study were to (1) identify feeding difficulties in infants with HLHS and d-TGA and (2) assess their growth in the first year of life. We performed a chart review of 27 consecutive infants with HLHS and 26 with d-TGA. Descriptive statistics were generated for demographic and clinical variables within each group and are presented as means ± standard deviations. HLHS and d-TGA groups were compared on time to achieving nutritional goals using the log rank test, on complication rate using the chi-square test, and on weight using the t-test. A significance level of 0.05 was used for all tests. Birth weight was similar for both the HLHS and d-TGA groups (3.19 ± 0.69 vs 3.35 ± 0.65 kg, respectively; p = 0.38). Infants with HLHS weighed less than those with d-TGA at l month (3.29 ± 0.58 vs 3.70 ± 0.60 kg, respectively; p = 0.021), 6 months (6.27 ± 1.06 vs 7.31 ± 1.02 kg, p = 0.003), and 12 months of age (8.40 ± 1.11 vs 9.49 ± 1.01 kg, p = 0.006). Time to achieving full caloric intake (at least 100 kcal/kg/day) for the HLHS group (24 ± 11.9 days) was significantly longer than for the d-TGA group (12.0 ± 11.2 days, p < 0.001). In addition, infants with HLHS had a higher incidence of feeding-related complications that those with d-TGA (48 vs 4%, respectively; p = 0.001). Compared to the d-TGA group, infants with HLHS weighed less at follow-up, took longer to reach nutritional goals, and had a much higher incidence of feeding-related complications. © 2007 Springer Science+Business Media, LLC.
Keywords: article; birth weight; caloric intake; clinical assessment; clinical feature; controlled study; feeding disorder; great vessels transposition; growth retardation; heart surgery; human; hypoplastic left heart syndrome; infant; major clinical study; occupational therapy; postoperative period; respiratory distress; speech therapy; vocal cord paralysis; body weight gain

Single ventricle repair in children with Down's syndrome - Wada, N.; Takahashi, Y.; Ando, M.; Park, I.-S.; Sasaki, T. (General Thoracic and Cardiovascular Surgery, 2008)
Objective. There is a paucity of information regarding appropriate management of children with Down's syndrome and a functional single ventricle. We report the results of bidirectional superior cavopulmonary shunts in six patients with Down's syndrome with a functional single ventricle. Methods. Between January 1991 and December 2004, we identified six patients with Down's syndrome among 263 who had undergone bidirectional superior cavopulmonary shunts (BCPSs). There were four males and two females. The age at BCPS ranged from 1 to 12 years (mean 4.3 ± 3.9 years), and body weight varied between 8.2 and 29.4 kg (mean 13.8 ± 7.8 kg). All six patients had an unbalanced complete atrioventricular septal defect, with right ventricular hypoplasia present in five and left ventricular hypoplasia in one. Results. There were no operative deaths, but one case required takedown of the BCPS. Except for this case, postoperative courses were generally uneventful. The median duration of follow-up was 46 months (range 12-80 months). Only two of five survivors after BCPS underwent a subsequent Fontan procedure, and one of these patients died of pulmonary hypertension post-operatively. The remaining three patients appeared to have significant risk factors for the Fontan procedure due to severe common atrioventricular valve regurgitation or persistent pulmonary vascular obstructive disease, including one who has completely dropped out from the Fontan track. Conclusion. Down's syndrome is a risk factor in patients with functionally single ventricle due to persistent pulmonary hypertension and airway obstruction. These results show that single ventricle repair in patients with Down's syndrome is accompanied with difficulties, and patient selection for the Fontan procedure should be done carefully. © 2008 The Japanese Association for Thoracic Surgery.
Keywords: article; cavopulmonary connection; child; clinical article; controlled study; Down syndrome; female; Fontan procedure; heart atrioventricular valve; heart single ventricle; human; lung hemodynamics; male; postoperative care; pulmonary hypertension; pulmonary vascular obstructive disease; risk factor; treatment outcome

Late follow-up of patients who underwent palliation for complex congenital heart disease in childhood - Hoffmann, A.; Wyler, F.; Günthard, J.; Grädel, E. (Congenital Heart Disease, 2008)
We report on a series of 12 patients with complex congenital heart disease who had reached adult life after surgical palliation in early childhood and who were systematically followed by clinical visits.: Patients were born between 1953 and 1979 and were followed up into 2007. All patients had complex lesions with single ventricle physiology and were palliated either by banding of the pulmonary artery or by creation of systemic-pulmonary shunts. Single operations were performed in 4 cases, and 8 patients had 1 or more further palliative interventions. Late corrective surgery and heart transplantation were performed in 1 patient each. Eight survivors reached a mean age of 36 years at follow-up (range 28-48), whereas 4 patients died at a mean age of 32 years (range 22-53). All patients were in New York Heart Association classes II and III. Complications during follow-up were bacterial endocarditis (3), cerebrovascular accidents (3), arrhythmias (3), need for pacemakers (2). Deaths occurred perioperatively at transplant (1), or were caused by sudden death (2), and hypoxia related to fall in blood pressure (1). Successfull pregnancies occurred in 3 patients with healthy (small) babies delivered by cesarean section in 2 of them, and vaginal delivery in 1. The course of life in these patients shows not only a wide spectrum with good quality of life in some of them but also a large number of potentially severe complications. Survival beyond 50 years is rare. © 2008, the Authors Journal compilation © 2008, Blackwell Publishing, Inc.
Keywords: adult; article; artificial heart pacemaker; bacterial endocarditis; cerebrovascular accident; child health; clinical article; congenital heart disease; female; follow up; heart arrhythmia; heart surgery; heart transplantation; human; hypoxia; long term care; male; mortality; palliative therapy; pregnancy outcome; priority journal; prognosis; survival rate; survival time

Neurodevelopmental outcomes after staged palliation for hypoplastic left heart syndrome - Tabbutt, S.; Nord, A.S.; Jarvik, G.P.; Bernbaum, J.; Wernovsky, G.; Gerdes, M.; Zackai, E.; Clancy, R.R.; Nicolson, S.C.; Spray, T.L.; Gaynor, J.W. (Pediatrics, 2008)
Objective. The goal was to determine the relative effects of underlying genetic factors and current management strategies on neurodevelopmental disabilities among one-year old survivors of palliation for hypoplastic left heart syndrome. methods. Children who underwent staged reconstruction for hypoplastic left heart syndrome and variants were assessed at 1 year of age by using a neuromuscular examination and the Bayley Scales of Infant Development II, which provide the Mental Development Index and the Psychomotor Development Index. The effects of perioperative, operative, and genetic variables on developmental scores were evaluated. results. The median birth weight was 3.3 kg (range: 2.1-4.5 kg). Eight-three patients (94%) underwent multiple operations with cardiopulmonary bypass during the first year of life (median: 2 operations). Seven patients (8%) required extracorporeal membrane oxygenation. Twenty-five patients (28%) had a confirmed or suspected genetic syndrome. At I year of age, the neuromuscular examination results were abnormal or suspect for 57 patients (65%). The median Mental Development Index-score was 90, and 10 patients (11%) had scores of <70 (2 SDs below the general population mean). The median Psychomotor Development Index score was 73, and 42 patients (48%) had scores of <70. In multivariate analyses, younger gestational age, the presence of a genetic syndrome, and the need for preoperative intubation had significant negative effects on neurodevelopmental outcomes. No association was found with operative factors, including duration of deep hypothermic circulatory arrest. conclusions. At 1 year of age, there was a significant incidence of neurodevelopmental disabilities in children with hypoplastic left heart syndrome and variants; motor scores were particularly concerning. Many children had suspected or confirmed genetic syndromes, which negatively affected neurodevelopmental outcomes. Surgical variables did not affect neurologic outcomes.
Keywords: article; Bayley Scales of Infant Development II; birth weight; cardiopulmonary bypass; chromosome aberration; deep hypothermic circulatory arrest; developmental disorder; developmental outcome; developmental screening; endotracheal intubation; ethnicity; extracorporeal oxygenation; female; genetic disorder; gestational age; head circumference; human; hypoplastic left heart syndrome; infant; Kabuki makeup syndrome; length of stay; major clinical study; male; mental development; metabolic acidosis; microcephaly; Norwood procedure; outcome assessment; priority journal; psychomotor development; risk factor; shock; statistical analysis; survival rate; Turner syndrome

Successful outpatient cardiac rehabilitation in an adult patient post-surgical repair for tricuspid valve atresia and hypoplastic right ventricle: A case study - Lichtman, S.W.; Caravano, M.; Schneyman, M.; Howell, B.; King, M.L. (Journal of Cardiopulmonary Rehabilitation and Prevention, 2008)
CLINICAL CASE: This case report documents outpatient cardiac rehabilitation (CR) in a 28-year-old woman born with transposition of the great vessels, tricuspid atresia, hypoplastic right ventricle, and an atrial septal defect. Surgical procedures were performed during childhood to correct these defects. In 2006, she underwent the following procedures: Fontan revision with a graft to an extracardiac total cavopulmonary connection; ASD creation; right atrial reduction; bidirectional Glenn shunt; right atrial and modified left atrial Maze procedures; and placement of an epicardial dual-chamber anti-tachycardia pacemaker. The patient was referred to CR because of postoperative complaints of fatigue, dyspnea on exertion, and low exercise tolerance. At intake, she underwent a cardiopulmonary stress test, measurement of percentage body fat, and completed the Medical Outcomes Survey 36-Item Short-Form Health Survey, Diet Intake Survey, and Center for Epidemiologic Studies Depression Scale. After completing 36 sessions, all outcomes demonstrated improvement with the exception of percentage dietary fat intake. DISCUSSION: Despite increasing numbers of patients with congenital heart disease (CHD) surviving into adulthood, exercise prescription in this population remains poorly delineated. In this case, possible physiologic limitations to exercise included diminished cardiac output secondary to low pressures and flow rates in the pulmonary arteries and veins because of the absence of a functioning right ventricle, limited chronotropic response, and severe deconditioning. SUMMARY: This case presents an adult patient who underwent surgical procedures to avoid heart transplantation. Despite severe CHD with many surgical procedures, and what is effectively a 2-chambered heart, she was able to successfully complete CR, graduate to home exercise, return to independent home living, and pursue her master's degree. © 2008 Lippincott Williams & Wilkins, Inc.
Keywords: adult; article; case report; dietary intake; echocardiography; exercise test; female; health survey; heart rehabilitation; heart surgery; human; hypoplastic left heart syndrome; outpatient; priority journal; tricuspid valve atresia

Psychological distress in parents of children with severe congenital heart disease: The impact of prenatal versus postnatal diagnosis - Brosig, C.L.; Whitstone, B.N.; Frommelt, M.A.; Frisbee, S.J.; Leuthner, S.R. (Journal of Perinatology, 2007)
Objective: The purpose of the study was to evaluate coping and psychological functioning of parents of children prenatally or postnatally diagnosed with congenital heart disease. Study Design: Parents of 10 infants prenatally diagnosed by fetal echocardiogram and 7 infants postnatally diagnosed with severe congenital heart disease completed the Brief Symptom Inventory (BSI) at the time of diagnosis, at the time of birth and 6 months after birth. Prenatal and postnatal groups were compared to each other and to BSI norms. Result: Although both groups scored higher than test norms at the time of diagnosis, they did not differ significantly from each other. Six months after birth, the postnatal group scores did not differ from test norms, but the prenatal group scores were still significantly higher than test norms. The severity of the child's heart lesion at diagnosis was related to parental distress levels; parents with children with more severe lesions had higher BSI scores. Conclusion: Results suggest the need to provide parents with psychological support, regardless of the timing of diagnosis. Parents of children with more severe lesions may be at risk for higher levels of psychological distress, particularly over time.
Keywords: aortic coarctation; aortic stenosis; article; Brief Symptom Inventory; childhood disease; clinical article; congenital heart disease; controlled study; coping behavior; disease severity; distress syndrome; echocardiography; Fallot tetralogy; female; great vessels transposition; heart single ventricle; high risk population; human; hypoplastic left heart syndrome; infant; lung vein drainage anomaly; male; parental attitude; prenatal diagnosis; psychosocial care; pulmonary valve stenosis; statistical significance

Hypoplastic left heart syndrome: Attitudes among pediatric residents and nurses towards fetal and neonatal management - Renella, P.; Chang, R.-K.R.; Ferry, D.A.; Bart, R.D.; Sklansky, M.S. (Prenatal Diagnosis, 2007)
Objective: To determine the attitudes of pediatric residents and nurses towards fetal/neonatal management of hypoplastic left heart syndrome (HLHS), and their basis. Methods: Pediatric residents and nurses from three cardiac centers completed a survey with hypothetical scenarios in which their own fetuses or newborns had HLHS. While Institution A performs many HLHS surgeries, Institution C performs very few. Results: A total of 43% of residents and 50% of nurses would terminate an affected pregnancy. More experience (4 to 7 years, p = 0.04; >7 years, p = 0.05) and employment at institution C (p = 0.04) predicted termination. Expected better quality of life (QOL) (p = 0.02) and five-year survival >50% (p = 0.06) predicted not terminating. Postnatally, 48% of residents and 68% of nurses would choose, or seriously consider, comfort care. Marriage (p = 0.04) and more experience (4 to 7 years, p = 0.04; >7 years, p = 0.02) predicted choosing comfort care. Asian/Pacific Islander descent (p = 0.01) and expected 5-year survival >50% (p = 0.02) predicted choosing surgery. Conclusions: Approximately one-half of the pediatric residents and nurses surveyed would choose termination of pregnancy or seriously consider declining neonatal surgery, if their own fetus or infant had HLHS. These attitudes reflect perceptions of long-term QOL and survival. These attitudes may be of interest to caregivers who care for HLHS patients. Copyright © 2007 John Wiley & Sons, Ltd.
Keywords: adult; article; Asian; controlled study; coronary care unit; experience; fetus; health survey; heart surgery; human; hypoplastic left heart syndrome; newborn; Pacific Islander; pediatric nurse practitioner; pediatrician; pediatrics; pregnancy termination; priority journal; quality of life; residency education; survival; treatment indication

Crouzon with acanthosis nigricans. Further delineation of the syndrome - Arnaud-López, L.; Fragoso, J.; Mantilla-Capacho, J.; Barros-Núñez, P. (Clinical Genetics, 2007)
Patients with Crouzon and acanthosis nigricans syndrome show craniofacial features similar to those observed in patients with classic Crouzon syndrome, in addition to acanthosis nigricans with peculiar characteristics. More severe physical manifestations, such as Chiari malformation, hydrocephalus, and atresia or stenosis of the choanas, which are unusual in individuals with classic Crouzon syndrome, are reported in these patients. The molecular abnormality associated with Crouzon syndrome with acanthosis nigricans (CAN) is a transition in the transmembrane domain of the FGFR3 gene that results in an Ala391Glu mutation. We describe two unrelated patients showing this mutation and compare their clinical features with those of other patients with CAN reported in the literature. In addition to craniosynostosis with crouzonoid facies and acanthosis nigricans (present in all patients), melanocytic nevi, choanal atresia or stenosis, hydrocephalus, Chiari malformations and oral abnormalities were observed in the majority of the 35 patients analyzed. Vertebral anomalies and conductive hearing loss were present with less frequency. Some characteristics considered typical of this condition (jaw cementomas, acanthomas and finger abnormalities) were absent in most of the patients. © 2007 The Authors Journal compilation © 2007 Blackwell Munksgaard.
Keywords: fibroblast growth factor receptor 3; membrane protein; acanthoma; acanthosis nigricans; adolescent; article; brachycephaly; case report; Chiari Frommel syndrome; clinical feature; computer assisted tomography; conduction deafness; craniofacial synostosis; Crouzon syndrome; Crouzon syndrome with acanthosis nigricans; differential diagnosis; exophthalmos; female; gene mutation; genetic screening; human; hydrocephalus; hypertelorism; hypochondroplasia; hypopigmentation; hypoplastic left heart syndrome; kidney failure; pigmented nevus; membranous glomerulonephritis; mental deficiency; mouth malformation; preschool child; priority journal; skeleton malformation; thorax radiography; vertebra malformation

Neuropsychological outcome in children with hypoplastic left heart syndrome. - Bordacova, L.; Docolomanska, D.; Masura, J. (Bratislavské lekárske listy, 2007)
OBJECTIVES: The purpose of this study is to review a single-institutional experience gained over one decade, to assess late neuropsychological outcome in patients as well as to determine Norwood operation risk factors that are related to patient and procedure and influence these results. BACKGROUND: The reports of first successful staged operation of hypoplastic left heart syndrome (HLHS) and its numerous modifications have improved the early survival also in patients with complex forms. Specifically, the identification of other specific risk factors related to patient or procedure in the first stage of palliation for HLHS may play a role in cognitive deficit. METHODS: Single-institutional, cross-sectional study of neurodevelopmental outcome. The mean age at testing was 6.9 +/- 0.3 years. There were 19 patients enrolled with completed psychological testing Standford-Binet test. RESULTS: The mean neurocognitive results were significantly below the population normative values. The mean full-scale IQ for the entire cohort was 84.1 +/- 8.2. The predictive factors are strongly associated with severe metabolic acidosis, low birth weight, hospital stay over 35 days, prolonged duration of DHA and aortic valve diameter playing an important role in the subsequent psychological outcome, especially in differential subsections of IQ scale (Tab. 2, Ref. 15). Full Text (Free, PDF) www.bmj.sk.
Keywords: article; child; cognitive defect; developmental disorder; follow up; human; hypoplastic left heart syndrome; intelligence; neuropsychological test; newborn; preschool child; psychological aspect; psychomotor performance

Implantation of stents to ensure an adequate interatrial communication in patients with hypoplastic left heart syndrome - Rupp, S.; Michel-Behnke, I.; Valeske, K.; Akintürk, H.; Schranz, D. (Cardiology in the Young, 2007)
Aims: To assess the feasibility of interatrial stenting for left atrial decompression in infants with hypoplastic left heart syndrome treated by a "hybrid-approach", with bilateral surgical banding of the pulmonary arteries and percutaneous stenting of the arterial duct. Patients and methods: We stented the atrial septum in 5 infants aged from 21 to 77 days, making the intervention as an elective procedure in 4, but as a rescue procedure in the fifth patient, who had a restrictive foramen. The stents, comprising 2 Jo-stents of 17 millimetres hand-crimped on a balloon catheter with dimensions of 10 by 20 millimetres, and 3 premounted Genesis stents with dimensions of 10 by 19 millimetres, were placed using a 6 French long or short sheath by femoral venous access. The stents were expanded under fluoroscopic guidance to create a slightly diabolo-shaped form that fitted the septum. Results: The percutaneous interventions were successfully performed in all cases, producing significant improvement in clinical condition after placement. The saturations of oxygen increased from an average of 64% plus or minus 18% to 88% plus or minus 7%, (p < 0.05). During a mean follow up of 2.5 months, without any anticoagulant therapy, there were no complications related to the stenting. Surgical removal of the stents was uneventful during reconstruction of the aortic arch and creation of a bidirectional cavopulmonary connection in 4 patients, and during cardiac transplantation in one. Conclusion: In the context of the hybrid approach, definitive decompression of the left atrium can be achieved by stenting the atrial septum in infants with hypoplastic left heart syndrome. Placement of the stents is safe and effective, with insertion in the form of a diabolo reducing the risk of dislocation, as well as embolisation of the stent. © 2007 Cambridge University Press.
Keywords: heparin; oxygen; aortic arch; artery catheterization; artery ligation; artery reconstruction; article; balloon catheter; conscious sedation; coronary stent; female; fluoroscopy; interatrial septum; heart left atrium pressure; heart transplantation; human; hypoplastic left heart syndrome; infant; intracardiac thrombosis; male; newborn; Norwood procedure; operation duration; oxygen saturation; percutaneous coronary intervention; pulmonary artery; risk reduction; surgical technique; Genesis; Jo-stent

Alagille syndrome with deletion 20p12.2-p12.3 and hypoplastic left heart - Robert, M.L.P.; Lopez, T.; Crolla, J.; Huang, S.; Owen, C.; Burvill-Holmes, L.; Stumper, O.; Turnpenny, P.D. (Clinical Dysmorphology, 2007)
We report a male patient born at 37-weeks gestation, weighing 1.885 kg (<0.4th centile). Shortly after birth, he was diagnosed with hypoplastic left heart syndrome for which he underwent a Norwood procedure. Subsequently, he developed problems with failure to thrive and developmental delay. At the age of 4 years his delay in growth and development led to further investigations, which revealed a small de-novo interstitial deletion of chromosome 20p12.2. JAGGED1 haploinsufficiency was confirmed by fluorescence in situ hybridization. Array-comparative genomic hybridization analysis confirmed and quantified an approximate 5.4 Mb interstitial deletion involving the chromosomal region 20p12.2-p12.3. This precise interstitial deletion has not been previously reported. Further clinical evaluation revealed posterior embryotoxon and butterfly vertebrae. He has normal liver function tests, facial features consistent with Alagille syndrome, and mild learning difficulties. To our knowledge this is the first report of Alagille syndrome associated with hypoplastic left heart syndrome. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: Alagille syndrome; article; case report; chromosome 20p; chromosome deletion; comparative genomic hybridization; developmental disorder; fluorescence in situ hybridization; haplotype; human; hypoplastic left heart syndrome; infant; learning disorder; liver function test; male; priority journal

Surgical management of Ebstein's anomaly. - Stulak, J.M.; Dearani, J.A.; Danielson, G.K. (Seminars in thoracic and cardiovascular surgery. Pediatric cardiac surgery annual, 2007)
Ebstein's malformation is a congenital anomaly of the tricuspid valve and right ventricle. Surgical repair of Ebstein's anomaly improves functional class and exercise tolerance, eliminates right-to-left intracardiac shunting (if present), and reduces the incidence of supraventricular tachyarrhythmias. As a result, quality of life and survival are improved. Because of the variable degree of malformation present, repair is predicated on favorable anatomic factors, most importantly the arrangement of the anterior leaflet of the tricuspid valve. When anatomic derangements threaten a durable tricuspid valve repair, valve replacement with protection of the conduction tissue and right coronary artery should be performed. The vast majority of patients can undergo a biventricular repair. The application of the bidirectional cavopulmonary anastomosis is reserved for patients with poor right ventricular function. Freedom from reoperation after tricuspid valve repair is similar when compared with valve replacement. In the current era, overall early mortality after surgical repair in children and adults has fallen to less than 3% in experienced centers. Surgical treatment of the symptomatic neonate remains a significant challenge, with approaches that include either a biventricular or single ventricle algorithm.
Keywords: adolescent; adult; age; aged; article; bioprosthesis; child; Ebstein anomaly; heart left ventricle function; heart right ventricle function; heart surgery; heart valve replacement; human; infant; methodology; middle aged; pathophysiology; preschool child; retrospective study; risk factor; supraventricular tachycardia; survival; suture technique; treatment outcome; United States

Risk factors for adverse events during cardiovascular magnetic resonance in congenital heart disease - Dorfman, A.L.; Odegard, K.C.; Powell, A.J.; Laussen, P.C.; Geva, T. (Journal of Cardiovascular Magnetic Resonance, 2007)
Purpose: To assess the incidence and severity of adverse events (AE) associated with cardiovascular magnetic resonance (CMR) in a large cohort of patients with congenital heart disease and to identify independent risk factors for their occurrence. Methods: AEs were prospectively recorded from October 2002 through December 2004 and graded by 3 independent observers for severity, preventability, and attributability. The rate of adverse events was analyzed for each candidate variable using Fisher's exact test and independent predictors were identified by multiple logistic regression analysis. Results: There were 22 AEs among 1334 CMR studies (1.6%); 14 (63.5%) minor, 7 (32%) moderate, and 1 (4.5%) major. General anesthesia (GA) was used in 274 studies (20.5%) with 12 AEs (4.4%, p < 0.001). There were 7 AEs (6.3%, p = 0.001) in 112 studies on hospitalized patients, 5 AEs (5.2%, p = 0.018) in 97 patients under 1 year of age, and 3 AEs (2.2%, p = 0.479) in 134 patients with functional single ventricle. The highest rate of AEs was noted in inpatients under GA (10.4%, p < 0.001); most were in the intensive care unit. Use of anesthesia (OR 3.91 [95% CI 1.46, 10.48] p = 0.007) and inpatient status (OR 3.56 [95% CI 1.16, 10.89], p = 0.026) were independent predictors of AEs. Conclusions: CMR in patients with congenital heart disease has a low rate of AEs. Use of GA and examinations on hospitalized patients are independent risk factors for AEs with the most acutely ill patients at highest risk. Copyright © 2007 Informa Healthcare USA, Inc.
Keywords: adenosine; epinephrine; anesthetic agent; diphenhydramine; dopamine; gadolinium pentetate; glycopyrronium; ipratropium bromide; salbutamol; steroid; adolescent; adult; aged; anxiety; article; bronchospasm; child; congenital heart disease; controlled study; disease severity; dysphagia; extravasation; female; Fisher exact test; general anesthesia; heat; hospital patient; human; hypotension; hypoxia; incidence; intensive care unit; lung edema; major clinical study; male; multivariate logistic regression analysis; nausea; nuclear magnetic resonance imaging; pneumothorax; priority journal; prophylaxis; prospective study; rash; risk factor; side effect; tachycardia; tachypnea; unspecified side effect; urticaria; vomiting

Psychosocial outcomes for preschool children and families after surgery for complex congenital heart disease - Brosig, C.L.; Mussatto, K.A.; Kuhn, E.M.; Tweddell, J.S. (Pediatric Cardiology, 2007)
The purpose of the current study was to assess the psychosocial outcomes of preschool-aged survivors (ages 3-6 years) of hypoplastic left heart syndrome (HLHS; n = 13) and transposition of the great arteries (TGA; n = 13). Parents completed the following measures: Pediatric Quality of Life Inventory, Impact on the Family Scale, Parenting Stress Index, Parent Behavior Checklist, and Child Behavior Checklist. Quality of life scores did not differ from those of healthy controls. Parents of children with HLHS reported more negative impact of the child's illness on the family and more parenting stress than parents of children with TGA. Parents of both groups of children were more permissive in their parenting style than parents of healthy controls. Children with HLHS had higher rates of attention and externalizing behavior problems than children with TGA. The results highlight the need for practitioners working with these children and families to ask about parental stress, family functioning, and behavioral expectations for the child in the context of routine medical/cardiac follow-up. © 2007 Springer Science+Business Media, LLC.
Keywords: age distribution; article; cardiopulmonary bypass; clinical article; congenital heart disease; controlled study; family functioning; female; follow up; great vessels transposition; hospitalization; human; hypoplastic left heart syndrome; length of stay; male; open heart surgery; outcome assessment; parental stress; preschool child; quality of life; rating scale; scoring system; social psychology; social status; statistical analysis

Clinico-pathological characteristics of congenital pulmonary lymphangiectasis: Report of two cases - Eom, M.; Yoo, D.C.; Youn, S.K.; Cho, M.-Y.; Jung, S.-H.; Han, Y.L. (Journal of Korean Medical Science, 2007)
Congenital pulmonary lymphangiectasis (CPL) is a rare, poorly documented disease, characterized by abnormal dilatation of pulmonary lymphatics without lymphatic proliferation. This disease is seen almost exclusively in infancy and early childhood. It can usually be divided into primary (congenital) and secondary forms. The primary form presents in neonates, and the patients mostly die due to the respiratory distress, shortly after birth. The authors experienced two cases of primary CPL in a 13-day-old male neonate and a one-day-old male neonate, showing prominent lymphatic dilatation in the septal, subpleural, and peri-bronchial tissue throughout both lungs. The latter case was associated with congenital cardiac anomaly including single ventricle. These are unique cases of CPL in Korea of which the diagnosis was established through post-mortem examination. Therefore, the authors report these two cases with primary CPL with a review of the literature. Copyright © The Korean Academy of Medical Sciences.
Keywords: article; case report; human; lung; lung disease; lymphangiectasis; lymphatic system; male; newborn; pathology

Safeguarding precarious survival: Parenting children who have life-threatening heart disease - Rempel, G.R.; Harrison, M.J. (Qualitative Health Research, 2007)
The purpose of this study is to describe the process of parenting a child with life-threatening heart disease. Despite advances in pediatric cardiac sciences, hypoplastic left heart syndrome remains difficult and controversial to treat. The Norwood surgical approach is a developing technology, and little is known about how mothers and fathers experience parenting a child who survives this treatment. Constructivist grounded theory informed this Canadian study that involved multiple interactive interviews with 9 mothers and 7 fathers of children with hypoplastic left heart syndrome who were at various stages of treatment. Extraordinary parenting in a context of uncertainty was evident as parents simultaneously safeguarded their child's precarious survival as well as their own survival. As technologically advanced treatment contributes to the survival of children with complex health conditions, health care professionals must consider how to promote and support parenting strategies that benefit the new survivors of technology as well as their families.
Keywords: adult; article; child care; child parent relation; congenital heart disease; female; grounded theory; health care personnel; health promotion; human; hypoplastic left heart syndrome; interview; male; medical technology; parental attitude; priority journal; surgical approach; survival; uncertainty

Safety and feasibility of inpatient exercise training in pediatric heart failure: A preliminary report - McBride, M.G.; Binder, T.J.; Paridon, S.M. (Journal of Cardiopulmonary Rehabilitation and Prevention, 2007)
PURPOSE: To determine the safety and feasibility of an inpatient exercise training program for a group of pediatric heart transplantation candidates on multiple inotropic support. BACKGROUND: Children with end-stage heart disease often require heart transplantation. Currently, no data exist on the safety and feasibility of an inpatient exercise training program in pediatric patients awaiting heart transplantation while on inotropic support. METHODS: Twenty ambulatory patients (11 male; age, 13.6 ± 3.2 years) were admitted, listed, and subsequently enrolled into an exercise training program while awaiting heart transplantation. Patient diagnoses consisted of dilated cardiomyopathy (n = 15), restrictive cardiomyopathy (n = 1), and failing single-ventricle physiology (n = 4). Inotropic support consisted of a combination of dobutamine, dopamine, or milrinone. Exercise sessions were scheduled three times a week lasting from 30 to 60 minutes and consisted of aerobic and musculoskeletal conditioning. RESULTS: Over 6.2 ± 4.2 months, 1,251 of a possible 1,508 exercise training sessions were conducted, with a total of 615 hours (26.3 ± 2.7 min/session) dedicated to low-intensity aerobic exercise. Reasons for noncompliance included a change in medical status, staffing, or patient cooperation. Two adverse episodes (seizures) occurred, neither of which resulted in termination from the program. No adverse episodes of hypotension or significant complex arrhythmias occurred. No complication of medication administration or loss of intravenous access occurred. CONCLUSION: Data from this study indicate that pediatric patients on inotropic support as a result of systemic ventricular or biventricular heart failure can safely participate in exercise training programs with relatively moderate to high compliance. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: dobutamine; dopamine; inotropic agent; milrinone; adolescent; adult; aerobic exercise; article; child; childhood disease; clinical article; congestive cardiomyopathy; exercise; female; health status; heart failure; heart rehabilitation; heart transplantation; hospital patient; human; infant; inotropism; male; patient compliance; priority journal; restrictive cardiomyopathy; risk benefit analysis; safety; seizure

Neurodevelopmental and neuroradiologic outcomes in patients with univentricular heart aged 5 to 7 years: Related risk factor analysis - Sarajuuri, A.; Jokinen, E.; Puosi, R.; Eronen, M.; Mildh, L.; Mattila, I.; Valanne, L.; Lönnqvist, T. (Journal of Thoracic and Cardiovascular Surgery, 2007)
Objective: Despite improved survival and neurodevelopmental outcome, children with hypoplastic left heart syndrome and other forms of univentricular heart remain at increased risk for cognitive, motor, and other neurologic deficits. Methods: We examined 27 children with hypoplastic left heart syndrome or other forms of univentricular heart at a median age of 5.70 years (range 4.99-7.51 years) and performed brain computed tomography or magnetic resonance imaging on 20. Possible risk factors were correlated with outcome. Results: Mean full-scale IQ among patients with hypoplastic left heart syndrome was 86.7; that among patients with other forms of univentricular heart was 89.1, with both differing significantly from the expected population mean (P = .015 and P = .029, respectively). Cerebral palsy was diagnosed in 1 of 7 patients with hypoplastic left heart syndrome and 2 of 20 with other forms of univentricular heart. Brain computed tomography or magnetic resonance imaging revealed ischemic changes and infarcts or atrophy in 5 of 8 patients who had undergone the Norwood procedure and in 2 of 12 of those who had not (P = .062). Abnormal computed tomographic findings correlated significantly with lower full-scale IQ (P = .045) and verbal IQ (P = .02). In the multiple linear regression model, diuresis the third day after the primary operation and cardiopulmonary bypass time in the bidirectional Glenn operation correlated significantly with the primary outcome of full-scale IQ. Conclusion: In children with univentricular heart, intellectual and neurologic deficits are common. Perioperative and postoperative risk factors related to the primary phase and bidirectional Glenn operation contribute to these deficits. © 2007 The American Association for Thoracic Surgery.
Keywords: article; brain atrophy; brain infarction; brain ischemia; cardiopulmonary bypass; cerebral palsy; child; clinical article; cognitive defect; computer assisted tomography; controlled study; diagnostic imaging; diuresis; heart single ventricle; human; hypoplastic left heart syndrome; intelligence quotient; motor dysfunction; nerve cell differentiation; neurologic disease; neuroradiology; Norwood procedure; nuclear magnetic resonance imaging; priority journal; risk assessment; surgical technique; survival

Physical activity levels in children and adolescents are reduced after the Fontan procedure, independent of exercise capacity, and are associated with lower perceived general health - McCrindle, B.W.; Williams, R.V.; Mital, S.; Clark, B.J.; Russell, J.L.; Klein, G.; Eisenmann, J.C. (Archives of Disease in Childhood, 2007)
Objectives: To determine physical activity levels in paediatric patients who underwent the Fontan procedure, and their relationship to functional status and exercise capacity. Study Design: We studied 147 patients (ages 7-18 years) at a median of 8.1 years after Fontan, as part of the Pediatric Heart Network cross-sectional study of Fontan survivors. Assessment included medical history, self-reported physical activity, parent-completed Child Health Questionnaire (CHQ), cardiopulmonary exercise testing and physical activity level measured by accelerometry (MTI Actigraph). Results: Measured time spent in moderate and vigorous activity was markedly below normal at all ages, particularly in females, and was not significantly related to self-reported activity levels, or to maximum VO2, VO2 at anaerobic threshold or maximum work rate on exercise testing. Lower measured activity levels were significantly related to lower perceived general health but not to self-esteem, physical functioning, social impact of physical limitations or overall physical or psychosocial health summary scores. Reduced exercise capacity was more strongly related than measured activity levels to lower scores in general health, self-esteem and physical functioning. Conclusions: Physical activity levels are reduced after Fontan, independent of exercise capacity, and are associated with lower perceived general health but not other aspects of functional status.
Keywords: accelerometry; adolescent; adult; anaerobic capacity; article; cardiopulmonary exercise test; controlled study; exercise; female; Fontan procedure; functional status; human; major clinical study; male; physical activity; preschool child; priority journal; questionnaire; school child; scoring system; self esteem; self report; social psychology

Surgical Management of Ebstein's Anomaly - Stulak, J.M.; Dearani, J.A.; Danielson, G.K. (Pediatric Cardiac Surgery Annual, 2007)
Ebstein's malformation is a congenital anomaly of the tricuspid valve and right ventricle. Surgical repair of Ebstein's anomaly improves functional class and exercise tolerance, eliminates right-to-left intracardiac shunting (if present), and reduces the incidence of supraventricular tachyarrhythmias. As a result, quality of life and survival are improved. Because of the variable degree of malformation present, repair is predicated on favorable anatomic factors, most importantly the arrangement of the anterior leaflet of the tricuspid valve. When anatomic derangements threaten a durable tricuspid valve repair, valve replacement with protection of the conduction tissue and right coronary artery should be performed. The vast majority of patients can undergo a biventricular repair. The application of the bidirectional cavopulmonary anastomosis is reserved for patients with poor right ventricular function. Freedom from reoperation after tricuspid valve repair is similar when compared with valve replacement. In the current era, overall early mortality after surgical repair in children and adults has fallen to less than 3% in experienced centers. Surgical treatment of the symptomatic neonate remains a significant challenge, with approaches that include either a biventricular or single ventricle algorithm. © 2007 Elsevier Inc. All rights reserved.
Keywords: acetylsalicylic acid; warfarin; article; cardiopulmonary bypass; cryoablation; Ebstein anomaly; exercise tolerance; Fontan procedure; heart right left shunt; heart right ventricle failure; heart surgery; heart valve replacement; human; intermethod comparison; pediatric surgery; postoperative period; postoperative thrombosis; quality of life; reoperation; supraventricular tachycardia; surgical anatomy; surgical mortality; surgical risk; surgical technique; survival rate; treatment indication; treatment outcome; tricuspid valve; vein anastomosis; aspirin

Neuropsychological outcome of children with asymmetric ventricles or unilateral mild ventriculomegaly identified in utero - Sadan, S.; Malinger, G.; Schweiger, A.; Lev, D.; Lerman-Sagie, T. (BJOG: An International Journal of Obstetrics and Gynaecology, 2007)
Design: To assess the neuropsychological outcome of children with asymmetric ventricles and unilateral ventriculomegaly identified in utero. Setting: Fetal neurology clinic. Population: We assessed 21 children with asymmetric ventricles (group 1) and 20 children with unilateral ventriculomegaly (group 2) identified in utero and compared them with a group of 20 children with symmetric ventricles using a formal neuropsychological tool: the Bayley Scale of Infant Development II (BSID-II). Main outcome measures: The group of children with unilateral ventriculomegaly scored significantly lower than the control group on the mental developmental index (MDI) and on the behaviour rating scale (BRS) but not on the psychomotor index. The group of children with asymmetric ventricles did not differ significantly from the control group on either the MDI or psychomotor developmental index but differed from the latter on the BRS. Fifteen percent of the children in the asymmetric ventriculomegaly group performed two SDs below average compared with 4% of children in the asymmetrical ventricles group and none of the control. Conclusion: Our results indicate that prenatally observed unilateral ventriculomegaly is a significant risk factor for developmental delay. The mental and motor outcome of children with asymmetric ventricles is similar to that of the control group, but these children are at a significant risk for behavioural abnormalities. © 2007 The Authors.
Keywords: article; bayley scale of infant development; behavioral science; controlled study; female; fetus echography; heart single ventricle; heart ventricle hypertrophy; human; major clinical study; male; medical assessment; mental development; neuropsychology; outcome assessment; prenatal diagnosis; preschool child; priority journal; psychomotor development; rating scale; risk factor; scoring system

Tension chylothorax in two pediatric patients - Wheeler, A.D.; Tobias, J.D. (Paediatric Anaesthesia, 2007)
Although the accumulation of gas is the most common cause of an expanding interpleural space, the presence of other structures or substances (hydrothorax, gastrothorax, hemothorax, urohemothorax, pyothorax, and chylothorax) under pressure may be sufficient to cause hemodynamic and respiratory compromise. We present two pediatric patients that developed hemodynamic and respiratory effects secondary to a chylothorax. The first patient presented in respiratory distress and cardiovascular collapse 4 weeks after a Fontan procedure. Placement of a chest tube resulted in the release of chyle under pressure and prompt resolution of hemodynamic and respiratory symptoms. The second patient was a 2100 g neonate who developed a chylothorax during an episode of sepsis following gastroschisis repair. On two separate occasions, the development of the chylothorax was associated with tachycardia, oliguria, and increased requirements during mechanical ventilation. Chest tube placement resulted in the release of chyle under pressure and resolution of the symptoms. These two cases demonstrate that chylothorax like pneumothorax can have deleterious effects on hemodynamic and respiratory function. © 2007 The Authors.
Keywords: article; artificial ventilation; case report; child; chyle; chylothorax; female; Fontan procedure; gastroschisis; human; lung hemodynamics; newborn; oliguria; pediatrics; pneumothorax; priority journal; respiratory distress; respiratory function; sepsis; shock; symptom; tachycardia; tension chylothorax; tube

Cardiovascular diseases in children - Tom-Revzon, C. (U.S. Pharmacist, 2007)
Cardiovascular diseases are becoming increasingly prevalent in children, due at least in part to the rise in childhood obesity. Public awareness is also increasing, and treatment options are improving. Pharmacists have the responsibility of counseling children and their caregivers about pharmacologic and nonpharmacologic therapies and interventions that can improve long-term prognosis. Adherence to complex medication regimens is key to optimal management. In cases of CHDs, for example, pharmacists can provide education about the rationale for drug therapy, and in cases of arrhythmia, they can obtain a thorough medication history to assist in diagnosis or avoidance. More important, pharmacists can stress the possibility of preventing the onset of cardiovascular diseases and encourage lifestyle changes that can help reduce the occurrence of hypertension and obesity.
Keywords: adenosine; epinephrine; amiodarone; antibiotic agent; atropine; benazepril; beta adrenergic receptor stimulating agent; calcium channel blocking agent; central stimulant agent; chlorothiazide; cholinergic receptor blocking agent; digoxin; endothelin receptor antagonist; flecainide; furosemide; hydrochlorothiazide; lidocaine; oxygen; phenothiazine; phosphodiesterase V inhibitor; procainamide; propranolol; prostaglandin; quinidine; salicylic acid; sotalol; spironolactone; theophylline; tricyclic antidepressant agent; unindexed drug; aortic coarctation; article; bacterial endocarditis; blood pressure regulation; bradycardia; cardiovascular disease; cardiovascular surgery; child health care; childhood mortality; congenital heart disease; Fallot tetralogy; great vessels transposition; heart arrhythmia; atrial fibrillation; heart atrium septum defect; heart failure; heart ventricle fibrillation; heart ventricle septum defect; heart ventricle tachycardia; hospitalization; human; hypertension; hypoplastic left heart syndrome; lifestyle modification; medical decision making; obesity; patent ductus arteriosus; patient counseling; patient monitoring; pharmaceutical care; pharmacist attitude; prevalence; prognosis; sinus tachycardia; supraventricular tachycardia; aldactone; hydrodiuril; inderal; lotensin

Adults Undergoing Cardiac Surgery at a Children's Hospital: An Analysis of Perioperative Morbidity - Rossano, J.W.; Smith, E.O.'.; Fraser Jr., C.D.; McKenzie, E.D.; Chang, A.C.; Hemingway, A.; Price, J.F.; Dickerson, H.A.; Mott, A.R. (Annals of Thoracic Surgery, 2007)
Background: Limited data exist regarding the perioperative morbidity profile of adults who have cardiac operations at pediatric facilities. Methods: A retrospective review (January 2000 to December 2004) of patients (aged 18 years or older) who underwent cardiac surgery at our pediatric institution was performed. Results: There were 149 cardiac operations performed in 135 patients. There were 2 early deaths. There were 70 preoperative noncardiac morbidities in 49 patients (36%) and 140 preoperative cardiac morbidities in 78 patients (58%). Preoperative arrhythmia (n = 76) and moderate or greater ventricular systolic dysfunction (n = 24) were most common. There were 51 postoperative adverse noncardiac events in 32 patients (24%). Renal insufficiency (> 0.5 mg/dL baseline change; n = 8) was most common. There were 53 postoperative adverse cardiac events in 44 patients (33%). Ventricular tachycardia (n = 13) was most common. Risk factors for postoperative adverse noncardiac events included preoperative histories of New York Heart Association (NYHA) class III or greater (p < 0.001), seizure (p = 0.04), and psychiatric disorder (p = 0.002). Risk factors for postoperative adverse cardiac events included older patient age (p = 0.001), preoperative functional single ventricle (p = 0.006), NHYA class III or greater (p = 0.003), atrial fibrillation/flutter (p < 0.001), and ventricular tachycardia or fibrillation (p = 0.04). Conclusions: Postoperative adverse events occur frequently when adults undergo cardiac operations at children's hospitals. Older patient age, preoperative arrhythmias, and preoperative NHYA class are predictors of postoperative adverse cardiac events. © 2007 The Society of Thoracic Surgeons.
Keywords: adult; article; bleeding; brachial plexus injury; cholelithiasis; congenital heart disease; controlled study; cyanosis; decubitus; depression; endocrine disease; epistaxis; female; genetic disorder; heart arrest; heart arrhythmia; atrial fibrillation; heart atrium flutter; heart single ventricle; heart surgery; heart ventricle fibrillation; heart ventricle tachycardia; human; hypertension; infection; kidney disease; kidney failure; liver dysfunction; lung disease; lung embolism; major clinical study; male; mental disease; morbidity; neurologic disease; cardiac rhythm management device; pericardial effusion; pleura effusion; pneumonia; pneumothorax; postoperative complication; predictor variable; priority journal; psychosis; risk factor; seizure; sepsis; sleep disordered breathing; cerebrovascular accident; supraventricular tachycardia; systolic dysfunction; tracheostomy; urinary tract infection; urine retention; vein thrombosis

Erratum: Quality of life in children with hypoplastic left heart syndrome (Acta Paediatrica, International Journal of Paediatrics (2007) 96, (53-57)) - Mellander, M.; Berntsson, L.; Nilsson, B. (Acta Paediatrica, International Journal of Paediatrics, 2007)
Keywords: erratum; error; priority journal

An extensive long term follow-up of a cohort of patients with hypoplasia of the left heart - Hagemo, P.S.; Skarbø, A.-B.; Rasmussen, M.; Fredriksen, P.M.; Schage, S. (Cardiology in the Young, 2007)
We report the results of follow-up of the complete cohort of Norwegian children born in the period from 1987 through 1998 in whom there was the intention to treat surgically hypoplasia of the left heart using the Norwood sequence of operations. Of the 54 children, 21 are alive. Of these, 15 have been extensively studied, while the medical state of all the remaining survivors is known from reports from other hospitals. Of the survivors, the majority have reasonably acceptable cardiac and haemodynamic function, but significant neurological and neuropsychological morbidity is identified within the group as a whole, which requires special attention from qualified personnel of various kinds. © 2007 Cambridge University Press.
Keywords: lamotrigine; valproic acid; article; artificial heart pacemaker; child; child death; clinical article; cohort analysis; controlled study; follow up; Fontan procedure; heart function; heart transplantation; hemodynamics; human; hypoplastic left heart syndrome; mental deficiency; morbidity; Norway; Norwood procedure; seizure; stent; survivor

Infant Heart Transplantation Ten Years Later-Where Are They Now? - Gandhi, S.K.; Canter, C.E.; Kulikowska, A.; Huddleston, C.B. (Annals of Thoracic Surgery, 2007)
Background: Many uncertainties regarding the fate of children undergoing heart transplantation as infants were present when we and others embarked on this program. Although no truly long-term results are available, a significant cohort of children has now reached preteen and early teenage status. We reviewed our group of infants transplanted more than 10 years ago to assess survival and quality of life as they approach their teenage years. Methods: We retrospectively reviewed the medical records of all infant (younger than 6 months of age) heart transplant recipients, transplanted between 1988 and 1995, to ascertain survival statistics, incidence of complications, and current health status. Results: A total of 42 patients were identified. The majority of these underwent transplantation for hypoplastic left heart syndrome. Eleven patients have died, 4 early and 7 late. The actual survival at 10 years is 76%. Twenty-seven of the 31 long-term survivors attend regular school; 4 are in special education classes owing to developmental delay. Five patients take medication for attention-deficit disorder. Malignancies have been discovered in 5, and 1 died secondary to this. Six patients have significant renal insufficiency, 1 of whom has undergone renal transplantation. One patient has undergone retransplantation for coronary artery disease. One patient required reoperation for supravalvar aortic stenosis. Other general medical problems that are being treated include sleep apnea (n = 1), hypertension (n = 5), and recurrent pneumonias (n = 1). Conclusions: Although these children require ongoing medical attention, including daily medications and regular follow-up visits, most have a satisfactory quality of life and behave much like normal children. © 2007 The Society of Thoracic Surgeons.
Keywords: aortic stenosis; article; attention deficit disorder; cause of death; clinical article; cohort analysis; coronary artery disease; follow up; health status; heart transplantation; human; hypertension; hypoplastic left heart syndrome; incidence; infant; kidney failure; kidney transplantation; pneumonia; priority journal; quality of life; recipient; recurrent disease; reoperation; retransplantation; retrospective study; school; sleep disordered breathing; special education; survival; systematic review

Health-related quality of life: A closer look at related research in patients who have undergone the Fontan operation over the last decade - Pike, N.A.; Evangelista, L.S.; Doering, L.V.; Koniak-Griffin, D.; Lewis, A.B.; Child, J.S. (Heart and Lung: Journal of Acute and Critical Care, 2007)
The advancements in surgical technique and perioperative care have significantly improved the survival of children with single ventricle (SV) congenital heart disease (CHD) over the past decade. The population who have undergone the Fontan operation are growing into adulthood and facing many unique challenges. Past research has focused on functional and neurodevelopmental outcomes with inferences made to health-related quality of life (HRQOL). With the population who have undergone the Fontan operation surviving into adulthood, little research has been directed toward the self-report of HRQOL in adolescents and young adults after surgical palliation. Questions still remain on how these patients will transition into adulthood and whether they will live normal productive lives. This article reviews the literature related to HRQOL in the SV subgroup of CHD. In addition, an overview of newly developed disease-specific HRQOL instruments is presented as well as limitations and future research in HRQOL of the SV Fontan population. © 2007 Mosby, Inc. All rights reserved.
Keywords: article; cognitive development; congenital heart disease; Fontan procedure; functional status; heart single ventricle; human; measurement; nerve cell differentiation; outcome assessment; priority journal; quality of life; self report

Quality of life in children with hypoplastic left heart syndrome - Mellander, M.; Berntsson, L.; Nilsson, B. (Acta Paediatrica, International Journal of Paediatrics, 2007)
Aim: To measure quality of life in children with hypoplastic left heart syndrome and their families. Methods: A questionnaire exploring socioeconomic status, structure and function of networks and psychological well-being was completed by the families of all 18 patients older than 2 years (age range 2.7-10.6). The results were compared with those of 180 healthy Swedish children matched for age and sex. Results: There were no significant differences between the groups in any of the aspects of socioeconomic status. Study group parents had not more available time for their child (p < 0.05) and more separations/divorces (p < 0.01). The patients had lower self-esteem (p < 0.05), more psychosomatic symptoms (p < 0.001) and lower peer acceptance (p < 0.01) than control children. Conclusion: With regard to psychological well-being, quality of life was significantly lower in children with hypoplastic left heart syndrome than in healthy controls. © 2006 The Author(s).
Keywords: age distribution; article; child; controlled study; divorce; family; female; health survey; human; hypoplastic left heart syndrome; major clinical study; male; Norwood procedure; patient satisfaction; priority journal; psychological well-being; quality of life; questionnaire; self esteem; sex ratio; social status; statistical significance; Sweden; treatment outcome

Psychological symptoms in patients after surgery for congenital cardiac disease - Geyer, S.; Norozi, K.; Zoege, M.; Kempa, A.; Buchhorn, R.; Wessel, A. (Cardiology in the Young, 2006)
Aims: We studied a population of patients with surgically corrected congenital cardiac disease to determine whether limitations in activity, impaired cardiac performance, and perception of body image have effects on psychological symptoms. Methods: We undertook medical examinations, and carried out standardized interviews, in 361 patients aged between 14 and 45 years with surgically corrected congenital cardiac disease. From this data, findings from 343 patients were suitable for analysis. Subjectively reported limitations in activity were classified according to the system proposed by the New York Heart Association, while cardiopulmonary capacity was used as the indicator of cardiac performance. The Brief Symptom Inventory was used for assessing psychological symptoms, such as somatization, obsession-compulsion, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation, and psychoticism. The Body Image Questionnaire was used to depict attitudes towards body image, which is assessed on the two subscales of rejection of the body and vitality. Multivariate regression analyses were conducted separately for females and males, taking into account age and socio-economic position. Results: Impairments of everyday activities had only a few substantial associations with psychological symptoms. No significant effects of cardiac functional capacity as a standardized physiological measure emerged. Psychological symptoms were strongly influenced by perceptions of body image, particularly if they rejected it, this holding particularly for males. There were no gender differences in terms of psychological symptoms. Conclusions: Limitations of activity, and impaired cardiac performance, have only minor effects on psychological symptoms in patients with surgically corrected congenital cardiac disease. The perception of body image was the strongest predictor, especially if patients rejected their body as a result of disfigurement or perceived deficiency. © 2006 Cambridge University Press.
Keywords: adolescent; adult; age; anxiety; aortic coarctation; article; body image; Brief Symptom Inventory; cardiopulmonary function; congenital heart disease; controlled study; daily life activity; depression; Fallot tetralogy; female; great vessels transposition; heart left right shunt; heart performance; heart single ventricle; heart surgery; hostility; human; interview; major clinical study; male; mental disease; multivariate analysis; obsessive compulsive disorder; paranoia; patent ductus arteriosus; phobia; postoperative period; prediction; psychosis; questionnaire; regression analysis; sex difference; socioeconomics; somatization

Current surgical therapy for Ebstein anomaly in neonates - Reemtsen, B.L.; Fagan, B.T.; Wells, W.J.; Starnes, V.A. (Journal of Thoracic and Cardiovascular Surgery, 2006)
Objective: Neonates with profound heart failure resulting from Ebstein anomaly have historically had poor outcomes. We report our institutional experience with the surgical management of Ebstein anomaly in severely symptomatic neonates. Methods: A retrospective review of all patients (n = 16) undergoing neonatal intervention for Ebstein anomaly between 1992 and 2005 has been carried out. The indications for operation were overt heart failure, cyanosis, and acidosis associated with tricuspid regurgitation, depressed right ventricular function, and severe cardiomegaly. The magnitude of cardiac enlargement was assessed by cardiothoracic ratio and Great Ormond Street ratio (area of right atrium + atrialized right ventricle/area of functional left atrium + left ventricle). The operative strategy was first to assess for the possibility of tricuspid valve repair with or without right ventricular outflow tract reconstruction. If this was not feasible, then right ventricular exclusion was performed by oversewing the tricuspid valve with a pericardial patch. A reduction atrioplasty was done and, depending on the extent of the atrialized portion of the right ventricle, plication was performed. A modified Blalock-Taussig shunt provided pulmonary blood flow. This univentricular approach (Starnes procedure) evolved to include a fenestration in the tricuspid valve patch to allow for right ventricular decompression. Analysis included overall and group-specific survival as well as the testing of perioperative clinical, morphologic, and surgical variables for correlation with mortality and morbidity. Results: Mean age and weight at operation were 8 ±10 days and 3.1 ± 0.4 kg. Tricuspid valve repair was undertaken in 3 patients with 1 requiring conversion to right ventricular exclusion 3 months after the initial operation. In those with right ventricular exclusion, the tricuspid valve patch was fenestrated in 10 and nonfenestrated in 3. One patient had heart transplant as the initial procedure. There were 5 hospital deaths (31%) and no late deaths among the survivors. Survival in the cohort with a fenestrated tricuspid valve patch was 80% (8/10) versus 33% (1/3) for the nonfenestrated group. This difference did not reach statistical significance, although the trend seems clinically important. There was no difference in the cardiothoracic ratio (0.82 fenestrated vs 0.84 nonfenestrated: P = .802) or the Great Ormond Street ratio (1.2 fenestrated vs 1.02 nonfenestrated: P = .477) between the two groups. Among the 9 survivors of right ventricular exclusion, 3 have had completion of their Fontan, and all 9 have undergone a bidirectional Glenn procedure. All operations including homograft placement in the right ventricular outflow tract, whether during repair or during right ventricular exclusion, ended in death. Conclusion: Right ventricular exclusion with a fenestrated tricuspid valve patch combined with right atrioplasty and right ventriculoplasty and a Blalock-Taussig shunt (Starnes procedure) has provided effective palliation for neonates presenting with critical Ebstein anomaly and a tricuspid valve that cannot be repaired. © 2006 The American Association for Thoracic Surgery.
Keywords: acidosis; article; Blalock Taussig shunt; cardiomegaly; clinical article; controlled study; correlation analysis; cyanosis; decompression surgery; disease severity; Ebstein anomaly; female; fenestration; Fontan procedure; Glenn shunt; heart atrioplasty; heart failure; heart left atrium; heart left ventricle; heart right atrium; heart right ventricle; heart right ventricle failure; heart right ventricle outflow tract; heart right ventricle outflow tract obstruction; heart surgery; heart valve surgery; heart ventriculoplasty; human; male; newborn; newborn surgery; overall survival; perioperative period; postoperative period; priority journal; Starnes procedure; surgical technique; survival rate; symptom; treatment indication; treatment outcome; tricuspid valve regurgitation

Surgical outcome of heterotaxy syndrome in a single institution - Takeuchi, K.; Murakami, A.; Hirata, Y.; Kitahori, K.; Doi, Y.; Takamoto, S. (Asian Cardiovascular and Thoracic Annals, 2006)
Heterotaxy syndrome encompasses a wide range of anatomical variants including poor pulmonary vascular development. Surgical outcome remains poor in this difficult subgroup. Between April 1996 and November 2004, 27 patients with visceral heterotaxy were enrolled in this study. The median age at presentation was 25 days. There were 11 patients with asplenia and 16 with polysplenia. There were 5 deaths (4 in patients with asplenia, 1 in a patient with polysplenia). All patients with asplenia were scheduled for single-ventricle repair, and 5 completed a modified Fontan procedure. Of the 16 patients with polysplenia, 8 completed 2-ventricle repair and 6 had a modified Fontan. In polysplenia, actuarial survival was 93.8% at 4 months, and remained constant thereafter. In asplenia, survival was 81.8% at 1 month, and 53.0% at 1 year. A significant correlation was found between nonconfluent pulmonary arteries and mortality. The medium-term result in polysplenia was satisfactory, but not in asplenia. Nonconfluent pulmonary arteries carry a high risk of mortality, and a strategy to create pulmonary vascular confluence and satisfactory pulmonary blood flow is mandatory.
Keywords: accessory spleen; article; asplenia; child; correlation analysis; female; Fontan procedure; heart surgery; heterotaxy syndrome; high risk population; human; infant; lung artery banding; pulmonary valve atresia; lung blood flow; lung blood vessel; male; outcome assessment; patient satisfaction; pulmonary valve stenosis; risk assessment; surgical mortality; survival time

The influence of congenital heart disease on psychological conditions in adolescents and adults after corrective surgery - Norozi, K.; Zoege, M.; Buchhorn, R.; Wessel, A.; Geyer, S. (Congenital Heart Disease, 2006)
Objective: The present study was designed to examine psychological characteristics of adolescents and adults with operated congenital heart disease (ACHD). Particularly it was to be examined whether cardiological parameters may be associated with subjectively perceived impairments and measures of psychological distress. Patients: A total of 361 men (209) and women (152) between 14 and 45years underwent medical checkups and an interview on psychological and sociological issues. Setting: The medical part consisted of a complete cardiological examination including the classification of residual symptoms according to the New York Heart Association (NYHA), and spiroergometry. The Brief Symptom Inventory was used for depicting current psychological and somatic symptoms. These were assessed on 9 subscales: somatization, obsession-compulsion, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation, and psychoticism. Results: The analyses revealed statistically significant associations between the degree of NYHA class and psychological symptoms. These findings could not be reproduced for physical fitness as measured by peak oxygen consumption. No gender differences emerged. Conclusions: Our results suggest that psychological measures of ACHD are not directly dependent on their physical fitness or on the severity of residual symptoms. Instead, patients'subjective appraisal of their disease severity and the conviction to what degree one can depend on the operated heart may be important determinants of psychological states. © 2006 the Authors; Journal compilation © 2006 Blackwell Publishing, Inc.
Keywords: oxygen; adolescent; adult; anxiety disorder; aortic coarctation; aortic valve disease; article; Brief Symptom Inventory; cardiovascular parameters; cardiovascular system examination; congenital heart disease; controlled study; depression; disease association; disease classification; disease severity; distress syndrome; ergometry; exercise test; Fallot tetralogy; female; fitness; Fontan procedure; great vessels transposition; heart left right shunt; heart single ventricle; heart surgery; hostility; human; human relation; interview; major clinical study; male; medical examination; mental health; obsessive compulsive disorder; oxygen consumption; paranoia; patient attitude; phobia; priority journal; psychological aspect; psychosis; psychosomatics; pulmonary valve disease; rating scale; sex difference; social psychology; somatization; spirometry; statistical significance; surgical technique; symptom

Successful selective intra-arterial thrombolytic therapy for embolic stroke in a patient with asplenia syndrome and unrepaired cyanotic congenital heart disease - Higashi, K.; Honda, T.; Tateno, S.; Kawasoe, Y.; Niwa, K.; Matsuda, S.; Ono, J.-I. (Congenital Heart Disease, 2006)
We report successful selective local intra-arterial thrombolytic therapy for thromboembolic occlusion of right middle cerebral artery in a patient with asplenia syndrome and unrepaired cyanotic congenital heart disease. © 2006 the Authors; Journal compilation © 2006 Blackwell Publishing, Inc.
Keywords: acetylsalicylic acid; digoxin; dipeptidyl carboxypeptidase inhibitor; diuretic agent; dopamine; enalapril; fibrinolytic agent; heparin; tissue plasminogen activator; warfarin; adolescent; aortic regurgitation; aphasia; article; asplenia; Blalock Taussig shunt; cardiomegaly; carotid arteriography; case report; computer assisted tomography; cyanotic heart disease; disease severity; drug selectivity; dyspnea; electrocardiography; guide wire; heart failure; heart single ventricle; hemiparesis; hospital discharge; human; internal carotid artery; pulmonary valve atresia; lung vein drainage anomaly; male; middle cerebral artery occlusion; pericardial effusion; peripheral edema; physical examination; priority journal; retina artery occlusion; thorax radiography; treatment outcome; two dimensional echocardiography; valvular heart disease; plasvata

National estimates and race/ethnic-specific variation of selected birth defects in the United States, 1999-2001 - Canfield, M.A.; Honein, M.A.; Yuskiv, N.; Xing, J.; Mai, C.T.; Collins, J.S.; Devine, O.; Petrini, J.; Ramadhani, T.A.; Hobbs, C.A.; Kirby, R.S. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2006)
BACKGROUND: In the United States, birth defects affect approximately 3% of all births, are a leading cause of infant mortality, and contribute substantially to childhood morbidity. METHODS: Population-based data from the National Birth Defects Prevention Network were combined to estimate the prevalence of 21 selected defects for 1999-2001, stratified by surveillance system type. National prevalence was estimated for each defect by pooling data from 11 states with active case-finding, and adjusting for the racial/ethnic distribution of US live births. We also assessed racial/ethnic variation of the selected birth defects. RESULTS: National birth defect prevalence estimates ranged from 0.82 per 10,000 live births for truncus arteriosus to 13.65 per 10,000 live births for Down syndrome. Compared with infants of non-Hispanic (NH) white mothers, infants of NH black mothers had a significantly higher birth prevalence of tetralogy of Fallot, lower limb reduction defects, and trisomy 18, and a significantly lower birth prevalence of cleft palate, cleft lip with or without cleft palate, esophageal atresia/tracheoesophageal fistula, gastroschisis, and Down syndrome. Infants of Hispanic mothers, compared with infants of NH white mothers, had a significantly higher birth prevalence of anencephalus, spina bifida, encephalocele, gastroschisis, and Down syndrome, and a significantly lower birth prevalence of tetralogy of Fallot, hypoplastic left heart syndrome, cleft palate without cleft lip, and esophageal atresia/tracheoesophageal fistula. CONCLUSIONS: This study can be used to evaluate individual state surveillance data, and to help plan for public health care and educational needs. It also provides valuable data on racial/ethnic patterns of selected major birth defects. © 2006 Wiley-Liss, Inc.
Keywords: anencephalus; anophthalmia; anus atresia; article; congenital malformation; cause of death; cleft lip; cleft lip palate; cleft palate; congenital heart disease; diaphragm hernia; Down syndrome; encephalocele; endocardial cushion defect; esophagus atresia; ethnic difference; Fallot tetralogy; gastroschisis; great vessels transposition; health care planning; health education; Hispanic; human; hypoplastic left heart syndrome; infant mortality; intestine atresia; intestine stenosis; limb reduction defect; microphthalmia; morbidity; omphalocele; prevalence; priority journal; race difference; spinal dysraphism; tracheoesophageal fistula; trisomy 13; trisomy 18; United States

Feasibility of using the national hospital discharge survey to estimate the prevalence of selected birth defects - Boulet, S.L.; Correa-Villaseñor, A.; Hsia, J.; Atrash, H. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2006)
BACKGROUND: Nationally representative data on the prevalence of certain birth defects are largely unavailable. We evaluated the feasibility of using data from the National Hospital Discharge Survey (NHDS) to describe the prevalence of selected birth defects. METHODS: All live births recorded in the NHDS during 1999-2001 were included. The prevalence for selected birth defects was calculated using weighted ratio estimators. Prevalence ratios comparing the NHDS estimates to published national estimates from the National Birth Defects Prevention Network (NBDPN) were calculated. RESULTS: With the exception of common truncus, the NHDS prevalence for the selected defects was consistently lower than the NBDPN estimates. The prevalence ratios ranged from 0.38 for trisomy 18 and anopthalmia/micropthalmia to 1.16 for common truncus. The NHDS prevalence estimates for spina bifida without anencephaly (PR 0.89, 95% CI: 0.57-1.22) and gastroschisis/omphalocele (PR 0.94, 95% CF: 0.48-1.40) most closely approximated the NBDPN estimates. CONCLUSIONS: NHDS data underestimate the prevalence of most birth defects. Additional research is needed to determine whether NHDS estimates may be useful for evaluating trends in certain conditions. Surveillance systems employing active case-finding continue to provide more accurate estimates of birth defects prevalence. © 2006 Wiley-Liss, Inc.
Keywords: accuracy; anencephalus; anophthalmia; anus atresia; article; congenital malformation; cleft lip; cleft lip palate; cleft palate; diaphragm hernia; Down syndrome; endocardial cushion defect; esophagus atresia; Fallot tetralogy; feasibility study; gastroschisis; great vessels transposition; hospital discharge; human; hypoplastic left heart syndrome; infant; intestine atresia; intestine stenosis; limb reduction defect; microphthalmia; newborn; omphalocele; prevalence; priority journal; spinal dysraphism; tracheoesophageal fistula; trisomy 13; trisomy 18

The management of hypoplastic left heart syndrome with aright aortic arch - Tatum, T.H.; Morell, V.O.; Park, S.C. (Cardiology in the Young, 2006)
The combination of hypoplastic left heart syndrome and a right-sided aortic arch is extremely rare and lethal. To the best of our knowledge, no patient with this combination has previously been reported as surviving initial palliation. The anatomic variant is associated with abnormalities in the arteries branching from the aortic arch, making it difficult to construct a reliable source of flow of blood to the lungs. We present here a patient with this combination who survived an initial Damus-Kay-Stansel procedure combined with placement of a conduit from the right ventricle to the pulmonary arteries, and who has subsequently undergone a successful bidirectional cavopulmonary anastomosis. We believe that the conduit placed from the right ventricle provides the most reliable source of flow of blood to the lungs at the time of initial palliation in this usual combination of cardiac lesions. © 2006 Cambridge University Press.
Keywords: polytetrafluoroethylene; anastomosis; aorta anomaly; aortic arch anomaly; aortic surgery; article; artificial ventilation; atresia; case report; cava vein; cocaine dependence; echocardiography; endocardial fibroelastosis; endotracheal intubation; heart catheterization; heart right ventricle; horseshoe kidney; human; hydramnios; hypoplastic left heart syndrome; lung blood flow; male; mitral valve stenosis; newborn; nuclear magnetic resonance imaging; polytetrafluoroethylene implant; pregnancy diabetes mellitus; prenatal care; pulmonary artery; respiratory distress; surgical technique

Design of a large cross-sectional study to facilitate future clinical trials in children with the Fontan palliation - Sleeper, L.A.; Anderson, P.; T. Hsu, D.; Mahony, L.; McCrindle, B.W.; Roth, S.J.; Saul, J.P.; Williams, R.V.; Geva, T.; Colan, S.D.; Clark, B.J. (American Heart Journal, 2006)
Background: Clinical trials in children with congenital heart disease are often limited by the absence of the following: (1) a primary outcome that can be observed in a reasonable period; (2) information regarding health-related quality of life; (3) knowledge of the correlation between health status and ventricular function and exercise performance; (4) a sufficient number of children at a single institution to provide adequate statistical power; and (5) procedural and management differences between and within institutions. Methods: The NHLBI-funded Pediatric Heart Network designed a cross-sectional study of children aged 6 to 18 years, from 7 pediatric clinical centers, who had undergone a Fontan procedure as treatment for congenital heart disease. Health-related quality of life was measured by the Child Health Questionnaire and the Congenital Heart Adolescent and Teenager Questionnaire. Ventricular function was assessed by maximal exercise testing, echocardiography, cardiac magnetic resonance imaging, and B-type natriuretic peptide. The study was designed to detect a correlation of R ≥ 0.30 between health status scores and measures of ventricular function and performance in a subcohort with all study measures completed. Results: A total of 1078 children were screened by chart review; 644 (60%) were eligible. The consent rate was 85% and 546 children were enrolled. Acquisition of echocardiograms, B-type natriuretic peptide, and health status was ≥94%; completion rates were lower for maximal exercise testing (76%) and cardiac magnetic resonance imaging (41%). Conclusions: This large study provides unique information regarding the relationship between health status and clinical measures in post-Fontan patients that will facilitate the design of future randomized trials. © 2006 Mosby, Inc. All rights reserved.
Keywords: brain natriuretic peptide; adolescent; adult; article; child; congenital heart disease; echocardiography; electrocardiogram; exercise test; female; fontan palliation; health status; heart surgery; heart ventricle function; human; informed consent; major clinical study; male; nuclear magnetic resonance imaging; pediatric hospital; priority journal; quality of life; questionnaire; screening; surgical approach

Unifocalization of Major Aortopulmonary Collaterals in Single-Ventricle Patients - Reinhartz, O.; Reddy, V.M.; Petrossian, E.; Suleman, S.; Mainwaring, R.D.; Rosenthal, D.N.; Feinstein, J.A.; Gulati, R.; Hanley, F.L. (Annals of Thoracic Surgery, 2006)
Background: Unifocalization of major aortopulmonary collateral arteries (MAPCAs) in pulmonary atresia with ventricular septal defect and intracardiac repair has become the standard of care. However, there are no reports addressing unifocalization of MAPCAs in single-ventricle patients. It is unknown whether their pulmonary vascular bed can be reconstructed and low enough pulmonary vascular resistance achieved to allow for superior or total cavopulmonary connections. Methods: We reviewed data on all patients with functional single ventricles and unifocalization procedures of MAPCAs. From 1997 to 2005, 14 consecutive children with various single-ventricle anatomies were operated on. Results: Patients had a median of three surgical procedures (range, 1 to 5). Two patients had absent, all others diminutive central pulmonary arteries, with an average of 3.5 ± 1.2 MAPCAs. Seven patients (50%) had bidirectional Glenn procedures, and 3 of these had Fontan procedures. Median postoperative pulmonary artery pressures measured 12.5 mm Hg (Glenn) and 14 mm Hg (Fontan), respectively. Six patients are alive today (46%), with 1 patient lost to follow-up. Three patients died early and 3 late after initial unifocalization to shunts. One other patient survived unifocalization, but was not considered a candidate for a Glenn procedure and died after high-risk two-ventricle repair. Another patient with right-ventricle-dependent coronary circulation died of sepsis late after Glenn. Conclusions: In selected patients with functional single ventricles and MAPCAs, the pulmonary vascular bed can be reconstructed sufficiently to allow for cavopulmonary connections. Venous flow to the pulmonary vasculature decreases cardiac volume load and is likely to increase life expectancy and quality of life for these patients. © 2006 The Society of Thoracic Surgeons.
Keywords: article; blood vessel; child; clinical article; collateral circulation; coronary artery blood flow; data analysis; female; follow up; Fontan procedure; Glenn shunt; heart right ventricle; heart single ventricle; heart surgery; heart ventricle; heart volume; heart work; human; infant; life expectancy; lung artery; lung artery pressure; lung blood vessel; major aortopulmonary collateral artery; male; newborn; postoperative period; priority journal; quality of life; sepsis; surgical technique; survival rate; time series analysis; unifocalization; vascular surgery

Atrial natriuretic peptide: Could it be a marker for postoperative recurrent effusions after fontan circulation in complex congenital heart defects? - Alkan, T.; Sarioǧlu, A.; Samanli, Ü.B.; Sarioǧlu, T.; Akçevin, A.; Türkoǧlu, H.; Paker, T.; Aytaç, A. (ASAIO Journal, 2006)
Fontan operation and its modifications are used for the physiological correction of complex congenital heart malformations with functionally single ventricle. Atrial natriuretic peptide (ANP), a physiological diuretic and vasodilator that-together with the effects of cardiopulmonary bypass-plays an important role in the augmentation of capillary permeability in Fontan patients. The rise in right atrial pressure and wall stress is an important stimulus for the release of ANP.ANP levels were measured before and early after surgery in Fontan group (n = 20) and control group (n = 20, patients with simple cardiac defects) to study its influence on and association with mean right atrial pressure, pulmonary vascular resistance (PVR), systemic vascular resistance, amount of drainage during early and late postoperative period, duration of intensive care unit and hospital stay, and need for colloid supplement.Early postoperative ANP values showed a negative correlation with PVR (r = -0.55) and total drainage (r = -0.88). There was no significant change in ANP during surgery or in the postoperative period in control patients.Reduction of PVR and maintenance of efficient urine output are important in the management of Fontan circulation. We conclude that high levels of ANP measured early after Fontan operation can be used as a marker for the successful establishment of Fontan circulation in patients with complex congenital heart defects. Copyright © American Society of Artificial Internal Organs.
Keywords: atrial natriuretic factor; adolescent; article; capillary permeability; child; clinical article; colloid; congenital heart malformation; controlled study; effusion; female; Fontan procedure; heart atrium pressure; hospitalization; human; intensive care unit; lung vascular resistance; male; surgical drainage; systemic vascular resistance

Mechanical valve replacement of the systemic atrioventricular valve in children - Reiss, N.; Blanz, U.; Breymann, T.; Kind, K.; Bairaktaris, A.; Körfer, R. (ASAIO Journal, 2006)
In children with systemic atrioventricular valve disease (SAVVD), reconstructive surgery is the primary goal. However, in cases with severely dysplastic valves or failed repair, valve replacement is the only option. The purpose of this study was to assess the early and late outcome following mechanical valve replacement in SAVVD. Between 1989 and 2003, 31 children underwent mechanical valve replacement (19 St. Jude Medical, 12 Carbomedics) in SAVVD (27 mitral, 3 tricuspid in corrected transposition of the great arteries, 1 common in an univentricular heart) at our institution. The ages ranged from 3 months to 15 years (mean 4 years) and body weight varied between 4.2 and 57 kg (mean 13.3 kg). The size of prostheses ranged between 16 and 31 mm (mean 23.9 mm). The main indication for valve replacement was severe insufficiency of left atrioventricular valve (84%); 84% of the patients had had a previous cardiac operation. The overall hospital mortality was 6.5% The mean follow up was 7.7 years (range 2-13 years). Ninety percent of children represent sinus rhythm, 87% are in NYHA class I. All patients were placed on a regimen of Phenprocoumon aiming to maintain the international normalized ratio (INR) between 3.0 and 4.0. Since 1994, INR self-management of oral anticoagulation was performed either by the patient or his or her parents. There was no anticoagulation-related complication in this patient group. Mechanical valve replacement in left atrioventricular valve disease carries a low operative risk across the spectrum of pediatric age despite previous operations in most cases. Long-term survival and quality of life are good in nearly all cases. The rate of anticoagulation-related complications is very low, especially when INR self management is performed. Copyright © American Society of Artificial Internal Organs.
Keywords: anticoagulant agent; phenprocoumon; adolescent; anticoagulation; article; child; clinical article; female; follow up; heart valve replacement; human; infant; international normalized ratio; male; mortality; outcome assessment; quality of life; school child; sinus rhythm; tricuspid valve disease

Early and long-term prognostic value of Troponin-I after cardiac surgery in newborns and children - Bottio, T.; Vida, V.; Padalino, M.; Gerosa, G.; Stellin, G. (European Journal of Cardio-thoracic Surgery, 2006)
Background: Troponin-I (Tn-I) is a well-recognized early postoperative marker for myocardial damage in adults and children. The present prospective study was undertaken to investigate whether a postoperative Tn-I value higher than 35 μg/l is able to predict long-term outcome as it does in early postoperative course, after surgery for congenital heart defects (CHD). Materials and methods: Five hundred and twenty patients (median age 11 months; male 54.7%: 284 patients) undergoing congenital heart defect repair on cardiopulmonary by-pass were prospectively updated in our database including postoperative Tn-I values. Seventy of them (13.4%) (mean age 2.6 ± 5.8 months) (70/520) experienced low output syndrome in the early postoperative period. According to the complexity of their malformations, we have arbitrarily divided these patients into two groups: group A included atrial and ventricular septal defects (13 patients), while group B included hypoplastic left heart syndrome, atrio-ventricular canal, transposition of great vessels, tetralogy of Fallot, double outlet right ventricle, truncus arteriosus, total anomalous venous return, and other combined diseases (57 patients). These patients are the object of our study. We reviewed clinical, laboratory, and echocardiographic data performed in the immediate postoperative course (within 24 h) and in the follow-up. Results: In this study, 13 patients died (13/70 patients; 18.5%), 12 in group B and 1 in group A. In deceased patients, mean Tn-I value was 130 ± 175 μg/l (CK-MB 570 ± 280 μg/l). Conversely, survivors showed a lower mean Tn-I value (25.5 ± 28.9 μg/l; CK-MB 76 ± 86 μg/l). Overall, Tn-I peak value was higher than 35 μg/l in 19 patients (19/70; 27.2%); among these, 9 died (median Tn-I was 163 ± 186 μg/l), whereas in survivors it was 73.4 ± 37 μg/l (p = 0.37). The remaining four patients who died had a median Tn-I value of 21 μg/l. When Tn-I exceeded 35 μg/l (>100 μg/l in two cases), at echocardiogram a severely depressed cardiac function was evident. Nevertheless, at long-term follow-up (12 ± 6 months), the echocardiogram showed an enhanced cardiac performance with an ejection fraction of 70 ± 8.5% in all; none of these patients presented with worsened ventricular function. Conclusion: Cardiac Tn-I is a specific and sensitive marker of myocardial injury after cardiac surgery and it may predict early in-hospital outcomes. However, by long-term echocardiographic analysis, cardiac Tn-I value looses its prognostic significance and therefore it is not a predictor of long-term ventricular dysfunction. © 2006 Elsevier B.V. All rights reserved.
Keywords: biological marker; creatine kinase MB; troponin I; arterial trunk; article; cardiopulmonary bypass; child; childhood; clinical examination; congenital heart malformation; controlled study; data base; disease marker; disease severity; echocardiography; Fallot tetralogy; female; follow up; forward heart failure; functional assessment; great vessels transposition; heart atrium septum defect; heart disease; heart ejection fraction; heart function; heart performance; heart right ventricle double outlet; heart surgery; heart ventricle function; heart ventricle septum defect; human; human tissue; hypoplastic left heart syndrome; laboratory test; major clinical study; male; newborn surgery; outcome assessment; pediatric surgery; postoperative period; prediction; priority journal; prognosis; quantitative analysis; sensitivity and specificity; surgical mortality; survival; vein malformation; venous return

Extracorporeal membrane oxygenation after stage I reconstruction for hypoplastic left heart syndrome - Ravishankar, C.; Dominguez, T.E.; Kreutzer, J.; Wernovsky, G.; Marino, B.S.; Godinez, R.; Priestley, M.A.; Gruber, P.J.; Gaynor, W.J.; Nicolson, S.C.; Spray, T.L.; Tabbutt, S. (Pediatric Critical Care Medicine, 2006)
OBJECTIVE: Although extracorporeal membrane oxygenation (ECMO) is an acceptable strategy for children with refractory cardiac dysfunction after cardiac surgery, its role after stage I reconstruction for hypoplastic left heart syndrome and its variants is controversial. Our objective is to describe the outcome of "nonelective" ECMO after stage I reconstruction. DESIGN: Retrospective case series. SETTING: Pediatric cardiac intensive care unit. PATIENTS: Infants placed on ECMO after stage I reconstruction from January 1998 to May 2005. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Of the 382 infants who underwent stage I reconstruction during the study period, 36 (9.4%) required ECMO in the postoperative period. There were 22 infants with hypoplastic left heart syndrome. Indications for ECMO included inability to separate from cardiopulmonary bypass in 14 and cardiac arrest in 22. Fourteen infants (38.8%) survived to hospital discharge. Nonsurvivors had longer cardiopulmonary bypass time (150.1 ± 70.0 mins vs. 103.9 ± 30.0 mins, p =. 01). 9/14 infants (64%) supported with ECMO> than 24 hrs after stage I reconstruction survived while only 5/22 infants (22%) requiring ECMO< 24 hrs of stage I reconstruction survived (p =. 02). Of note, all five infants diagnosed with an acute shunt thrombosis were early survivors. Mean duration of ECMO was 50.1 ± 12.5 hrs for survivors and 125.2 ± 25.0 for nonsurvivors (p =. 01). 7/14 early survivors are alive at a median follow-up of 20 months (2-78 months). CONCLUSIONS: In our experience, ECMO after stage I reconstruction can be life saving in about a third of infants with otherwise fatal conditions. It is particularly useful in potentially reversible conditions such as acute shunt thrombosis and transient depression of ventricular function. Copyright © 2006 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: acute disease; article; cardiopulmonary bypass; clinical article; controlled study; extracorporeal oxygenation; female; follow up; heart surgery; hospital discharge; human; hypoplastic left heart syndrome; infant; male; postoperative care; postoperative period; priority journal; retrospective study; shunt thrombosis; surgical technique; treatment duration; treatment indication; treatment outcome

Fetal-to-neonatal maladaptation - Sinha, S.K.; Donn, S.M. (Seminars in Fetal and Neonatal Medicine, 2006)
Although the majority of newly born babies will establish normal respiratory and circulatory function without help, 1-2% might run into difficulties because of a disturbance in the normal adaptive processes required for a smooth transition from intrauterine to extrauterine life. An understanding of the normal and abnormal perinatal physiology is important to appreciate the practical differences in the approach to caring for such babies, and also for avoiding actions that might be detrimental in the longer term. © 2006 Elsevier Ltd. All rights reserved.
Keywords: analgesic agent; anesthetic agent; corticosteroid; magnesium sulfate; nitric oxide; prostacyclin; sedative agent; sildenafil; surfactant; tolazoline; vasodilator agent; anemia; aortic stenosis; article; artificial ventilation; baby; birth; birth injury; central nervous system malformation; circulation; congenital diaphragm hernia; cyanotic heart disease; cystic adenomatoid malformation; extracorporeal oxygenation; fetal hemorrhage; fetus hypoxia; heart right left shunt; human; hypercapnia; hyperviscosity syndrome; hypoplastic left heart syndrome; hypotension; hypoventilation; hypoxemia; infection; life; lung hypoplasia; maladjustment; meconium aspiration; metabolism; nervous system injury; neuromuscular disease; newborn care; oxygen therapy; perinatal period; pneumonia; prenatal period; pulmonary hypertension; respiration depression; respiratory acidosis; respiratory distress; respiratory distress syndrome; respiratory function; resuscitation; sepsis; thermoregulation; tricuspid valve atresia

Wall shear stress is the primary mechanism of energy loss in the Fontan connection - Moyle, K.R.; Mallinson, G.D.; Occleshaw, C.J.; Cowan, B.R.; Gentles, T.L. (Pediatric Cardiology, 2006)
Long-term outcome following the Fontan operation may be affected by the amount of energy lost as blood flows through the anastomosis geometry. A method for detailed quantification of energy loss is applied to computational simulations of the flow in an atriopulmonary and a total cavopulmonary model. Five types of flow (near wall, slow recirculation, medium speed vortices, collision, and streamlined flow) are identified and their energy losses quantified. The presence of recirculation regions decreases the efficiency of the atriopulmonary model, and a region of increased energy loss is seen in the collision region in the total cavopulmonary model. However, the most significant energy loss is through wall shear stress, which is maximal in areas where there is rapid, near wall flow. © Springer Science+Business Media, Inc. 2006.
Keywords: adult; anastomosis; article; blood flow; blood flow velocity; energy expenditure; female; flow kinetics; Fontan procedure; hemodynamics; human; male; model; school child; shear stress; simulation; vortex motion

Maternal birthplace and major congenital malformations among New York Hispanics - Zhu, M.; Druschel, C.; Lin, S. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2006)
BACKGROUND: Little is known about the association between maternal nativity and congenital malformations among Hispanics living in the United States. METHODS: We conducted a cross-sectional study to investigate the association between maternal nativity and various congenital malformations among singleton live-births born to Hispanic women in New York from 1993 to 2001. Birth certificates, used to identify maternal birthplace, were linked with congenital malformation registry files to obtain birth defects outcome. We examined how the risk of birth defects varied by maternal birthplace by estimating the adjusted odds ratios (aORs) using logistic regression. RESULTS: A foreign maternal birth showed statistically negative associations with overall congenital malformations (aOR, 0.70; 95% CI, 0.68-0.73), cardiovascular defects (aOR, 0.85; 95% CI, 0.77-0.93), central nervous system defects (aOR, 0.76; 95% CI, 0.63-0.91), and multiple defects (aOR, 0.80; 95% CI, 0.74-0.86). Specifically, foreign-born Hispanic women were statistically at reduced risk to deliver live babies with cleft palate (aOR, 0.56; 95% CI, 0.40-0.80), atresia and stenosis of rectum or anus (aOR, 0.58; 95% CI, 0.35-0.97), and craniosynostosis (aOR, 0.71; 95% CI, 0.51-0.99). Hispanic mothers born in Puerto Rico had a similar risk of delivering children with birth defects compared to U.S.-born Hispanic mothers. In contrast, Hispanic mothers born in Mexico, or Cuba and Central and South America were at reduced risk of delivering infants with overall congenital malformations (aOR, 0.64; 95% CI, 0.60-0.67) and (aOR, 0.65; 95% CI, 0.63-0.68), respectively. CONCLUSIONS: Foreign-born Hispanic mothers had a slightly lower risk to deliver live-born singleton infants with major congenital malformations than did U.S. born Hispanic mothers. © 2006 Wiley-Liss, Inc.
Keywords: illicit drug; anus atresia; aortic coarctation; article; birth certificate; congenital malformation; birthplace; cardiovascular malformation; central nervous system malformation; child; cigarette smoking; cleft lip; cleft palate; colon stenosis; congenital malformation; craniofacial synostosis; Cuba; drinking behavior; Fallot tetralogy; great vessels transposition; Hispanic; human; hypoplastic left heart syndrome; infant; limb malformation; logistic regression analysis; major clinical study; Mexico; multiple malformation syndrome; nullipara; prenatal care; priority journal; Puerto Rico; register; socioeconomics; South and Central America; spinal dysraphism; spontaneous abortion; tracheoesophageal fistula; United States

Right-Sided Maze Procedure for Atrial Tachyarrhythmias in Congenital Heart Disease - Stulak, J.M.; Dearani, J.A.; Puga, F.J.; Zehr, K.J.; Schaff, H.V.; Danielson, G.K. (Annals of Thoracic Surgery, 2006)
Background: Congenital heart disease (CHD) that causes right atrial dilatation is commonly associated with atrial flutter and/or fibrillation (AFl/F). To reduce late recurrence of AFl/F in patients undergoing repair of CHD, we utilized a concomitant right-sided maze procedure. Methods: From 1993 to 2003, 99 patients with CHD and associated AFl/F underwent a concomitant right-sided maze procedure at the time of CHD repair. Ages ranged from 9 to 72 years (median, 43 years). Atrial flutter and/or fibrillation was paroxysmal in 81 and chronic in 18; duration ranged from less than 1 month to 39.5 years (median, 2.9 years). Primary cardiac diagnoses were Ebstein anomaly (n = 47), other congenital tricuspid regurgitation (n = 19), univentricular heart (n = 11), isolated atrial septal defect (ASD, n = 8), tetralogy of Fallot (n = 8), and other (n = 6). Results: Other concomitant procedures included tricuspid valve repair or replacement (n = 70), ASD closure (n = 39), and pulmonary valve procedures (n = 18). There were 6 early deaths. At hospital dismissal, 83 patients were free of AFl/F and 63 were in sinus rhythm. Follow-up in 87 of the 93 early survivors extended up to 8 years (mean, 2.7 years). There were 4 late deaths, all from noncardiac causes. Of the 83 known late survivors, 77 (93%) were free of AFl/F. Eighty-two of the 83 survivors were in New York Heart Association class I or II. Conclusions: In patients with AFl/F associated with CHD, a concomitant right-sided maze procedure at the time of intracardiac repair is effective in reducing late recurrent AFl/F. Most patients enjoy an excellent quality of life. © 2006 The Society of Thoracic Surgeons.
Keywords: adult; age distribution; aged; article; congenital heart disease; controlled study; disease duration; Ebstein anomaly; Fallot tetralogy; female; follow up; atrial fibrillation; heart atrium flutter; heart atrium septum defect; heart single ventricle; heart surgery; heart valve replacement; heart valve surgery; hospital discharge; human; major clinical study; male; patient coding; priority journal; pulmonary valve; recurrent disease; right sided maze procedure; school child; sinus rhythm; supraventricular tachycardia; survival time; tricuspid valve regurgitation

Optimal timing of the second stage of palliation for hypoplastic left heart syndrome facilitated through home monitoring, and the results of early cavopulmonary anastomosis - Ghanayem, N.S.; Tweddell, J.S.; Hoffman, G.M.; Mussatto, K.; Jaquiss, R.D.B. (Cardiology in the Young, 2006)
For children with hypoplastic left heart syndrome, contemporary management over three stages includes a window of high risk for sudden death between the initial stage of palliation, the Norwood operation itself, and the second stage, creation of the bidirectional superior cavopulmonary connection. The risk is highest at a time when patients have been discharged from the hospital to grow and prepare for the second stage, and has persisted despite the remarkable improvements in immediate postoperative and hospital survival after the initial surgery. Potential contributing factors to the increased vulnerability to sudden death between the stages include the limited circulatory reserve inherent in the parallel circulations supported by a functionally univentricular heart, the reliance on a prosthetic shunt which is susceptible to thrombosis, and congenital or acquired anatomical cardiovascular abnormalities such as aortic atresia, residual obstruction in the aortic arch, tricuspid valvar insufficiency, or right ventricular dysfunction. © 2006 Cambridge University Press.
Keywords: oxygen; aggressiveness; arterial oxygen saturation; article; body growth; body weight; child; child health care; elective surgery; Fontan procedure; home monitoring; human; hypoplastic left heart syndrome; pulmonary arteriovenous fistula; observational study; palliative therapy; risk assessment; treatment outcome; body weight gain

Current insights regarding neurological and developmental abnormalities in children and young adults with complex congenital cardiac disease - Wernovsky, G. (Cardiology in the Young, 2006)
Over a decade ago, I co-authored a review in Cardiology in the Young regarding neurological outcomes following surgery for congenital cardiac disease. In that review, I placed much emphasis on the conduct of cardiopulmonary bypass, and its role in neurodevelopmental disabilities. Much has been learned in the intervening years regarding the multifactorial causes of abnormal school-age development, in particular, the role of prenatal, perioperative, socioeconomic, and genetic influences. In this update, I will highlight some of the recent advances in our understanding of the protean causes of neurological, behavioral, and developmental abnormalities in children and young adults with complex forms of congenital cardiac disease. In addition, I will summarize the current data on patients at particular high-risk for adverse neurodevelopmental outcomes, specifically those with a functionally univentricular heart who have had staged reconstruction with ultimate conversion to the Fontan circulation. © 2006 Cambridge University Press.
Keywords: academic achievement; adult; article; attention; brain malformation; cardiopulmonary bypass; central nervous system disease; child; child behavior; clinical study; congenital heart disease; developmental disorder; encephalomalacia; environmental factor; experimental design; fetus circulation; Fontan procedure; handwriting; heart arrest; heredity; hospital patient; human; hypothermia; intensive care; intraoperative period; laboratory test; longitudinal study; mental function; microcephaly; neurologic disease; outpatient care; postoperative period; preoperative period; prevalence; quality of life; reoperation; risk assessment; surgical risk; treatment outcome

Current management of late failure after classic Fontan modifications: Fontan conversions - Erek, E.; Yalcinbas, Y.K.; Sarioglu, A.; Sarioglu, T. (Thoracic and Cardiovascular Surgeon, 2006)
Background: Re-establishment of Fontan circulation by eliminating the drawbacks of classic Fontan modifications has been proposed recently to improve the functional class and quality of life of patients with failed Fontan circulation. Methods: Five patients underwent extracardiac and lateral tunnel Fontan conversion due to failure of the Fontan circulation, after classic Fontan modifications. All of the patients were female and mean age was 10.2 ± 2.2 years (range: 8-14 years). Previous Fontan modifications were atriopulmonary anastomosis in 3 and Kawashima operation in 2 patients. Time to re-operation for Fontan conversion was 6 ± 1.5 years (range: 4-8 years). Indications for re-operation were right heart failure, right atrial dilatation, and intractable atrial arrhythmias in patients with previous atriopulmonary anastomosis, progressive hypoxia and exercise intolerance in patients with previous Kawashima operation due to pulmonary arteriovenous fistulas. Previous atriopulmonary anastomoses were converted to intra-atrial or lateral tunnel Fontan operation with modified right atrial Maze procedure. Extracardiac Fontan completion was carried out after previous Kawashima operations by redirection of hepatic veins to the lungs. Results: There was no mortality and no major morbidity. All patients were discharged from the hospital in good condition and in sinus rhythm. No prolonged or recurrent effusions were observed. On follow-up, all patients were in sinus rhythm and had NYHA class I functional capacity. In two Kawashima patients, SpO2 gradually increased from 60% to 90% six months after the operation. Discussion: We suggest that Fontan conversion should be considered in patients with previous atriopulmonary anastomosis, when right atrial dilatation or intractable atrial arrhythmias with deteriorating functional status develops. Redirection of hepatic venous flow to lungs induces regression of pulmonary arteriovenous fistulas and improves arterial saturation in patients with previous Kawashima operation. © Georg Thieme Verlag KG.
Keywords: adolescent; arterial oxygen tension; arteriovenous fistula; article; clinical article; deterioration; exercise tolerance; female; Fontan procedure; heart atrium arrhythmia; heart atrium enlargement; heart failure; heart function; heart muscle ischemia; heart rhythm; human; kawashima operation; liver vein; lung blood flow; morbidity; mortality; priority journal; quality of life; reoperation; school child; surgical technique; treatment indication; vein blood flow

Relationship of patient and medical characteristics to health status in children and adolescents after the Fontan procedure - McCrindle, B.W.; Williams, R.V.; Mitchell, P.D.; Hsu, D.T.; Paridon, S.M.; Atz, A.M.; Li, J.S.; Newburger, J.W. (Circulation, 2006)
Background - After the Fontan procedure, patients are at risk for suboptimal health status related to their complex healthcare experience, physiological limitations, medical complications, and guarded long-term prognosis. Methods and Results - In the Pediatric Heart Network cross-sectional study of Fontan survivors 6 to 18 years of age, parents completed the Child Health Questionnaire, and scores were related in multivariable analysis to patient and medical characteristics obtained from medical record review. For 537 patients (mean age at study, 11.9 years; 60% male) with a median age at Fontan of 2.8 years (range, 0.7 to 14.6 years), parent-reported patient morbidities included deficits in vision in 33%, speech in 27%, and hearing in 7%, as well as problems with attention in 46%, learning in 43%, development in 24%, behavior in 23%, anxiety in 17%, and depression in 8%. Child Health Questionnaire summary scores were significantly lower than the US population sample for Physical Functioning (mean Z score, -0.47±1.19; P<0.001) and Psychosocial Functioning (-0.28±1.08; P<0.001). Parent-reported medical conditions and long-term and current medical problems explained the greatest amount of variation in the Physical Functioning scores. Parent-reported patient conditions, including behavior, learning, anxiety, and attention problems and depression, explained the greatest amount of variation in the Psychosocial Functioning scores. Lower family income had a negative impact on both Physical and Psychosocial Functioning. Conclusions - There are deficits in health status in children and adolescents after the Fontan procedure. Strategies to address this problem might emphasize coordinated and effective prevention, detection, and management of noncardiac and psychosocial conditions, as well as specific targeting of patients from low-income households. © 2006 American Heart Association, Inc.
Keywords: adult; allergy; anxiety; article; asthma; attention disturbance; behavior disorder; child; depression; developmental disorder; follow up; Fontan procedure; health status; hearing disorder; human; income; learning disorder; major clinical study; parent; priority journal; prognosis; social psychology; speech disorder; United States; visual disorder

Conversion of the failed Fontan circulation - Backer, C.L.; Deal, B.J.; Mavroudis, C.; Franklin, W.H.; Stewart, R.D. (Cardiology in the Young, 2006)
Many patients with a functional univentricular heart were treated in the 1970s and 1980s, using an atriopulmonary connection to create the Fontan circulation. Although this procedure, in many patients, was initially successful, and provided arterial saturations of oxygen close to normal, as these patients were followed over the years, in some cases they developed significant complications. One complication of the atriopulmonary connection is progressive right atrial dilation, which leads to atrial arrhythmias, such as atrial flutter or fibrillation. The combination of these two problems leads to low cardiac output, diminished quality of life, and poor categorization within the classification of the New York Heart Association. This, and other issues, has led most centres to abandon the atriopulmonary connection as a means of creating the Fontan circulation in favour of the lateral tunnel with cavopulmonary connections, or the extracardiac conduit.
Keywords: antiarrhythmic agent; oxygen; adolescent; arterial oxygen saturation; article; artificial heart pacemaker; cardiopulmonary bypass; child; controlled study; cryosurgery; death; disease classification; follow up; Fontan procedure; graft rejection; graft survival; health care organization; heart assist device; heart atrium arrhythmia; heart atrium enlargement; atrial fibrillation; heart atrium flutter; heart output; heart single ventricle; heart transplantation; hemodialysis; human; kidney failure; kidney transplantation; length of stay; liver failure; major clinical study; outcome assessment; peritoneal dialysis; quality of life; reentry tachycardia; surgical equipment; surgical technique; treatment failure; treatment indication; treatment outcome; United States; AT 500; Surgifrost

Intra-atrial tissue plasminogen activator infusion for prosthetic valve thrombosis - Seltzer, S.M.; Reed, M.D.; Siwik, E.S. (Catheterization and Cardiovascular Interventions, 2006)
Thrombosis is a well-known and life-threatening complication of prosthetic mechanical valves. Therapy typically requires medical thrombolysis or surgical thrombectomy/valve replacement. We report the case of a thrombosed atrioventricular valve in a young boy with complex congenital heart disease, which was successfully treated with direct intra-atrial infusion of recombinant tissue plasminogen activator after failed attempts at systemic therapy. We present this treatment as an alternative to conventional medical therapy. © 2005 Wiley-Liss, Inc.
Keywords: acetylsalicylic acid; alteplase; heparin; polytetrafluoroethylene; tissue plasminogen activator; warfarin; anticoagulation; artery graft; article; asplenia; bleeding; cardioversion; case report; fibrinolytic therapy; fluoroscopy; Fontan procedure; great vessels transposition; heart atrioventricular valve; heart single ventricle; heart valve prosthesis; heart valve regurgitation; hematoma; hemodynamics; human; lung artery pressure; lung vein drainage anomaly; male; mitral valve atresia; patient compliance; prothrombin time; pulmonary valve stenosis; school child; thrombectomy; thrombosis; transesophageal echocardiography

Current outcomes and risk factors for the Norwood procedure - Stasik, C.N.; Goldberg, C.S.; Bove, E.L.; Devaney, E.J.; Ohye, R.G. (Journal of Thoracic and Cardiovascular Surgery, 2006)
Objective: Tremendous strides have been made in the outcomes for hypoplastic left heart syndrome and other functional single-ventricle malformations over the past 25 years. This progress relates primarily to improvements in survival for patients undergoing the Norwood procedure. Previous reports on risk factors have been on smaller groups of patients or collected over relatively long periods of time, during which management has evolved. We analyzed our current results for the Norwood procedure with attention to risk factors for poor outcome. Methods: A single-institution review of all patients undergoing a Norwood procedure for a single-ventricle malformation from May 1, 2001, through April 30, 2003, was performed. Patient demographics, anatomy, clinical condition, associated anomalies, operative details, and outcomes were recorded. Results: Of the 111 patients, there were 23 (21%) hospital deaths. Univariate analysis revealed noncardiac abnormalities (genetic or significant extracardiac diagnosis, P = .0018), gestational age (P = .03), diagnosis of unbalanced atrioventricular septal defect (P = .017), and weight of less than 2.5 kg (P = .0072) to be related to hospital death. On multivariate analysis, only weight of less than 2.5 kg and noncardiac abnormalities were found to be independent risk factors. Patients with either of these characteristics had a hospital survival of 52% (12/23), whereas those at standard risk had a survival of 86% (76/88). Conclusions: Although improvements in management might have lessened the effect of some of the traditionally reported risk factors related to variations in the cardiovascular anatomy, noncardiac abnormalities and low birth weight remain as a future challenge for the physician caring for the patient with single-ventricle physiology. Copyright © 2006 by The American Association for Thoracic Surgery.
Keywords: Alagille syndrome; bile duct atresia; body weight; brain artery aneurysm; cerebrovascular accident; controlled study; corpus callosum agenesis; Costello syndrome; death; demography; female; gestational age; heart atrium septum defect; heart single ventricle; human; kidney dysplasia; kidney failure; lung dysplasia; major clinical study; male; McKusick Kaufman syndrome; newborn; Norwood procedure; priority journal; review; risk factor; treatment outcome; Turner syndrome

Fetal echocardiography service in Qatar: Establishment, challenges and outcome - Ahmed, B.; El Sisi, A.; Khenyab, N.; Saleh, N.; Al Mansoori, Z.; Gendi, S.; El Said, H.; Numan, M. (Qatar Medical Journal, 2006)
A prospective observational study at the newly established Fetal Medicine Unit, Hamad Hospital, Qatar, evaluated the impact of the service on the detection rate of critical congenital heart defects, patterns of referral and subsequent yield for structural congenital heart disease in a population with a significant proportion of high risk factors. Of 391 pregnant females examined between January 2003 and December 2004, 58 (14.8%) had fetal cardiac abnormalities of which 23 (5.8% of total referrals) had major structural malformations of the heart. Cases of fetal congenital heart disease had further evaluation using real time three-dimensional echocardiography (RT3DE) which is new equipment in the paediatric cardiology department. All cases with cardiac defects whether minor or major had follow up fetal echocardiography. Neonatal echocardiography confirmed the diagnosis in all cases with major defects (100% specificity). False positive cases that were found to be normal post natal were 1% of the total cases referred (12% of cases with congenital malformation). False negative cases were 1% and all had a small ventricular septal defect (VSD) except for one Down's syndrome with a very large VSD. Three patients needed urgent Caesarean section (CS) deliveries, one with complete heart block (HB) and two with supraventricular tachycardia (SVT). One patient traveled abroad as the fetus had left isomerism and major cardiac defects and complete HB. Fifteen newborns had to receive prostaglandin based on thefetal diagnosis before being seen by paediatric cardiologists. There was no termination of pregnancy due to major cardiac defects even in cases of HLHS. The preliminary results of this clinic are very satisfactory and have affected favorably the outcome of the new-borns with congenital heart defects. It is hoped that the results of this study will encourage more referrals to the FMU.
Keywords: antiarrhythmic agent; prostaglandin; adult; article; artificial heart pacemaker; cesarean section; complete heart block; congenital heart disease; congenital heart malformation; diagnostic accuracy; disease predisposition; Down syndrome; early diagnosis; Ebstein anomaly; echocardiography; false negative result; false positive result; female; fetus; fetus echography; fetus hydrops; follow up; great vessels transposition; health care delivery; health care quality; heart right ventricle double outlet; heart single ventricle; heart surgery; heart ventricle septum defect; high risk population; hospital department; human; hypoplastic left heart syndrome; pulmonary valve atresia; major clinical study; newborn; newborn disease; observational study; outcome assessment; patient referral; pregnancy termination; prenatal diagnosis; prospective study; Qatar; rhabdomyoma; risk factor; sensitivity and specificity; supraventricular tachycardia; three dimensional echocardiography; travel

Non-invasive assessment of ventricular force-frequency relations in the univentricular circulation by tissue Doppler echocardiography: A novel method of assessing myocardial performance in congenital heart disease - Cheung, M.M.H.; Smallhorn, J.F.; McCrindle, B.W.; Van Arsdell, G.S.; Redington, A.N. (Heart, 2005)
Objective: To describe the first clinical application of a novel tissue Doppler derived index of contractility, isovolumic acceleration (IVA), in the assessment of the ventricular myocardial force-frequency relation (FFR) in the univentricular heart (UVH). Design: Prospective study. Setting: Tertiary referral centre. Interventions: Non-invasive assessment of the myocardial FFR by tissue Doppler echocardiography during atrial pacing. Results: IVA was used to measure the FFR of the systemic ventricle in patients with structurally normal hearts and in patients with UVHs. Basal IVA of the normal hearts (mean (SD) 1.9 (0.3) m/s2) was significantly greater than that of UVHs in patients with a dominant right ventricle (RV) (1.0 (0.3) m/s2) or left ventricle (LV) (0.8 (0.7) m/s2; p < 0.05 for both). Neither the absolute nor percentage change from basal to peak values of IVA with pacing differed between the three groups. Peak force developed by the normal LV was significantly greater than that of the UVH, dominant LV group but not different from that of the UVH, dominant RV group. Conclusion: Contractility at basal heart rate is depressed in patients with UVH compared with the normal LV. Analysis of ventricular FFRs exposes further differences in myocardial contractility. There is no evidence that contractile function of the dominant RV is inferior to that of the dominant LV over a physiological range of heart rates.
Keywords: article; child; clinical article; congenital heart disease; controlled study; Doppler echocardiography; heart atrium pacing; cardiac index; heart left ventricle; heart muscle contractile force; heart muscle contractility; heart performance; heart rate; heart right ventricle; heart single ventricle; human; priority journal

Specific issues after extracardiac fontan operation: Ventricular function, growth potential, arrhythmia, and thromboembolism - Chowdhury, U.K.; Airan, B.; Kothari, S.S.; Talwar, S.; Saxena, A.; Singh, R.; Subramaniam, G.K.; Pradeep, K.K.; Patel, C.D.; Venugopal, P. (Annals of Thoracic Surgery, 2005)
Background. The purpose of this study was to define the prevalence of specific sequelae after extracardiac Fontan operation. Methods. Sixty-five consecutive patients undergoing extracardiac Fontan operation were studied for mortality, Fontan failure, systemic ventricular function, supraventricular arrhythmias, thromboembolism, and growth potential. Age was 3 to 31 years (mean ± standard deviation, 9.4 ± 1.8; median, 7 years). The conduits were constructed of polytetrafluoroethylene (n = 50), and "viable" in situ pericardium (n = 15). The patients underwent serial echocardiogram, dynamic radionuclide studies, and cardiac catheterization. Results. Operative mortality was 3%, and the incidence of conduit thrombosis was 4.6%. There was paradoxic filling of the right lung after femoral injection of the radiotracer in all cases of conduit obstruction. Perioperative and late postoperative supraventricular arrhythmias were observed in 9.2% and 4.7% of patients, respectively. Risk factors for supraventricular arrhythmias included systemic ventricular dysfunction (p = 0.000), heterotaxy syndrome (p = 0.008), systemic venous anomalies (p = 0.015), and previous bidirectional Glenn operation (p = 0.017). At a mean follow-up of 77 ± 2 months (range, 8 to 79 months), there were no late deaths (actuarial survival at 79 months, 96.9% ± 0.02%). Serial echocardiograms demonstrated evidence of growth of the viable tunnels. Postoperatively, there was transient depression of ejection fraction in all patients (p = 0.000). Conclusions. Supraventricular arrhythmias after extracardiac Fontan are more common in patients with heterotaxy syndrome, bilateral superior venae cavae, systemic ventricular dysfunction, and those undergoing completion Fontan operation. The viable tunnel may emerge as an optimal alternative by virtue of reduction of supraventricular arrhythmias, elimination of the need for anticoagulation, and addressing the issue of growth potential in selected patients. © 2005 by The Society of Thoracic Surgeons.
Keywords: polytetrafluoroethylene; radioisotope; tracer; adolescent; adult; article; child; controlled study; death; echocardiography; follow up; Fontan procedure; growth; heart catheterization; heart ejection fraction; heart supraventricular arrhythmia; heart ventricle function; heterotaxy syndrome; human; lung; major clinical study; mortality; pericardium; perioperative period; postoperative complication; postoperative period; priority journal; risk factor; surgical mortality; surgical technique; survival; thromboembolism; thrombosis; treatment failure

Familial biventricular myocardial noncompaction associated with Ebstein's malformation - Šinkovec, M.; Koželj, M.; Podnar, T. (International Journal of Cardiology, 2005)
Background: Noncompaction of the ventricular myocardium is a rare congenital cardiomyopathy characterized by numerous excessively prominent trabeculations and deep intertrabecular recesses. Noncompaction of the ventricular myocardium is most often an isolated cardiac malformation presenting as a sporadic disease. Associated cardiac anomalies are present in some patients. We report a family with three adult males from consecutive generations having a biventricular form of noncompaction of the myocardium. Two of the patients have an associated Ebstein's malformation of the tricuspid valve. Methods: Clinical evaluation and follow-up, electrocardiography, echocardiography, heart catheterization, coronary angiography, contrast cineventriculography, and magnetic resonance imaging. Results and conclusions: The association of noncompaction of the ventricular myocardium and Ebstein's malformation has not been reported so far. We believe that both defects were caused by a developmental arrest of the right ventricular myocardium. Echocardiography is the diagnostic modality of choice in patients and in the male relatives, irrespective of their clinical status. Thromboembolic events, cardiac rhythm disorders and heart failure mandate treatment. Anticoagulation treatment and implantation of cardioverter-defibrillator pacemaker have to be strongly considered in these patients. © 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: acetylsalicylic acid; amiodarone; bisoprolol; contrast medium; dipeptidyl carboxypeptidase inhibitor; furosemide; glipizide; heparin; metformin; spironolactone; warfarin; adolescent; adult; angiocardiography; anticoagulation; aphasia; article; artificial heart pacemaker; biventricular myocardial noncompaction; cardiomegaly; cardiomyopathy; case report; cerebrovascular accident; color Doppler flowmetry; defibrillator; diabetes mellitus; disease association; drug hypersensitivity; drug safety; echocardiography; electrocardiography; familial disease; family; follow up; health status; heart arrest; heart atrium flutter; heart catheterization; heart cineventriculography; heart development; heart left bundle branch block; heart left ventricle hypertrophy; heart ventricle tachycardia; hemiparesis; human; lung congestion; male; medical assessment; middle cerebral artery occlusion; mitral valve regurgitation; nuclear magnetic resonance imaging; priority journal; pulmonary hypertension; relative; supraventricular tachycardia; thorax injury; thorax radiography; thromboembolism; traffic accident; tricuspid valve atresia; tricuspid valve regurgitation; aspirin

Temporary decompression of the right ventricle to assess the right ventricle-dependent coronary circulation in pulmonary atresia with intact ventricular septum - Iwai, S.; Kishimoto, H.; Kawata, H. (Japanese Journal of Thoracic and Cardiovascular Surgery, 2005)
We repaired a case of pulmonary atresia with intact ventricular septum in which the blood supply to the left anterior descending coronary artery depended on the right ventricle. At the time of a bidirectional Glenn operation, total cardiopulmonary bypass with venous drainage from the right atrium was performed in order to evaluate the safety of right ventricular decompression required for a planned Fontan operation. We confirmed the dependence of the coronary perfusion on the right ventricle by demonstrating transient depression of the ST segment in the epicardial electrocardiogram during temporary decompression of the right ventricle. To prevent ischemic myocardial damage, we then performed an extracardiac Fontan operation with a temporary venous shunt and without cardiopulmonary bypass.
Keywords: angiography; article; cardiopulmonary bypass; case report; coronary artery blood flow; decompression; echocardiography; electrocardiogram; Fontan procedure; heart muscle injury; heart muscle ischemia; heart right ventricle; interventricular septum; human; infant; left anterior descending coronary artery; pulmonary valve atresia; male

Obstetrics - Harris, R.D. (Ultrasound Quarterly, 2005)
Keywords: adult; Alagille syndrome; amniocentesis; article; autopsy; case report; CATCH 22 syndrome; chromosome 22q; chromosome deletion; cleft palate; clinical feature; clubfoot; congenital heart malformation; congenital malformation; developmental disorder; differential diagnosis; DiGeorge syndrome; face dysmorphia; Fallot tetralogy; family history; female; fetus echography; fluorescence in situ hybridization; Goldenhar syndrome; heart ventricle septum defect; heterozygote; human; hypoplasia; hypoplastic left heart syndrome; incidence; kidney malformation; mental disease; newborn; newborn death; palatopharyngeal incompetence; patent ductus arteriosus; polydactyly; priority journal; recurrence risk; short stature; Smith Lemli Opitz syndrome; syndactyly; syndrome VACTERL; thymus disease; thymus hypoplasia; velocardiofacial syndrome; vertebra malformation

Risperidone treatment of three seriously medically ill children with secondary mood disorders - Bealke, J.M.; Meighen, K.G. (Psychosomatics, 2005)
Keywords: chloral hydrate; chlorpromazine; dexamethasone; diphenhydramine; haloperidol; hypnotic sedative agent; lorazepam; mercaptopurine; methotrexate; morphine sulfate; phenytoin; risperidone; vincristine; acute lymphoblastic leukemia; aggression; agitation; article; brain infarction; case report; clinical feature; computer assisted tomography; congenital heart disease; critical illness; drug response; electroencephalogram; feeding disorder; fever; Fontan procedure; heart single ventricle; human; hypertension; hypoxia; irritability; male; mood disorder; nuclear magnetic resonance imaging; preschool child; seizure; tachycardia; tachypnea

What is the perceived quality of life of adults with congenital heart disease and does it differ by anomaly? - Simko, L.C.; McGinnis, K.A. (The Journal of cardiovascular nursing, 2005)
Adults with congenital heart disease (CHD) represent a growing population of patients thanks to the medical and surgical advances which enable at least 85% of children to survive to adulthood. These advances may create quality-of-life (QoL) issues not previously considered. The purpose of this cross-sectional study of 124 adults with CHD was to describe their QoL as a basis for providing appropriate information, counseling, and anticipatory guidance. Thirteen patients had single ventricle physiology (SVP), 43 had cyanotic lesions with 2 ventricle repairs, and 68 had acyanotic CHD. On the basis of Sickness Impact Profile (SIP) scores, individuals with SVP had worse QoL than did those with cyanotic lesions (with 2 ventricle repairs) and acyanotic anomalies (SIP = 9.98 vs 4.61 and 3.76). SIP scores were statistically significantly different between those with SVP and those with acyanotic anomalies (P = .02). For all groups, the areas of life most affected were work and sleep and rest. Participants with SVP saw themselves as having the poorest QoL.
Keywords: adult; analysis of variance; article; attitude to health; classification; comparative study; congenital heart malformation; cross-sectional study; cyanosis; daily life activity; disabled person; female; health status; hospitalization; human; male; needs assessment; nurse attitude; nursing assessment; patient education; psychological aspect; quality of life; questionnaire; Sickness Impact Profile; United States

Hybrid procedures in pediatric cardiac surgery - Bacha, E.A.; Hijazi, Z.M. (Pediatric Cardiac Surgery Annual, 2005)
Hybrid pediatric cardiac surgery is an emerging field that combines skills and techniques used by pediatric cardiac surgeons and interventional pediatric cardiologists. This article describes the emerging indications and techniques in hybrid pediatric cardiac surgery and discusses potential future applications. It focuses on peratrial and perventricular septal defect closure, intraoperative stenting, hybrid stage I palliation for hypoplastic left heart syndrome, and percutaneous valve implantation. © 2005 Elsevier Inc. All rights reserved.
Keywords: artery compression; article; heart atrium septum defect; heart surgery; heart valve replacement; heart ventricle septum defect; human; hypoplastic left heart syndrome; intraoperative period; mediastinitis; palliative therapy; pediatric surgery; pleura effusion; postoperative complication; skill; stent; surgeon; surgical technique; treatment indication

Late outcomes in patients with surgically treated congenital heart disease - Schultz, A.H.; Wernovsky, G. (Pediatric Cardiac Surgery Annual, 2005)
Optimizing late outcomes should be the end result of improvements in medical and surgical care for congenital heart disease (CHD). In addition to mortality, significant morbidities after surgery for CHD need to be considered. These include the need for reintervention, cardiovascular complications, exercise limitations, neurocognitive morbidities, effects on pregnancy, difficulty obtaining insurance, need for chronic medications, and impaired functional status and quality of life. Long-term outcome studies are difficult to perform, and their interpretation is complicated by intervening changes in management. Specific discussion of long-term follow-up of tetralogy of Fallot, D-transposition of the great arteries, and hypoplastic left heart syndrome illustrates the myriad management changes over the last three decades, the challenges in predicting outcomes for recent patients, and the need for ongoing initiation of long-term follow-up studies. © 2005 Elsevier Inc. All rights reserved.
Keywords: article; cardiovascular disease; child; cognitive defect; congenital heart disease; endocarditis; exercise; Fallot tetralogy; follow up; great vessels transposition; health insurance; health status; heart arrhythmia; heart failure; heart surgery; heart transplantation; heart ventricle failure; human; hypoplasia; medical care; morbidity; prediction; pregnancy; quality of life; reoperation; surgical mortality; treatment outcome

Persistent plastic bronchitis in a child after cardiac surgery - Peleg, U.; Schwartz, S.; Sirota, G.; Hochman, I.; Cohen, D.; Picard, E. (Israel Medical Association Journal, 2005)
Keywords: acetylcysteine; antibiotic agent; azithromycin; bronchodilating agent; deoxyribonuclease; diuretic agent; mucolytic agent; oxygen; steroid; tissue plasminogen activator; warfarin; article; atelectasis; Blalock Taussig shunt; bronchitis; bronchoscopy; cardiopulmonary arrest; case report; childhood disease; chylothorax; coughing; cyanosis; cyanotic heart disease; death; diaphragm paralysis; dyspnea; female; Fontan procedure; heart catheterization; heart single ventricle; heart surgery; human; human cell; hypoxia; physiotherapy; pneumonia; preschool child; psychomotor retardation; respiratory distress; respiratory failure; surgical technique; thorax radiography; tricuspid valve atresia; coumadin

Early results of extracardiac Fontan procedure with autologous pericardial tube conduit - Yalcinbas, Y.K.; Erek, E.; Salihoglu, E.; Sarioglu, A.; Sarioglu, T. (Thoracic and Cardiovascular Surgeon, 2005)
Background: Different types of conduits are used for extracardiac Fontan procedure. The use of autologous pericardial tube as an alternative conduit for connecting the inferior vena cava to the pulmonary artery is investigated. Methods: We performed 25 extracardiac Fontan procedures by using pericardial tube between June 2000 and October 2003. Fifteen patients were male. Mean age and weight were 7.6 ± 4.9 years (range 3 to 24 years) and 22.8 ± 10.4 kg (range 12-50 kg), respectively. Results: All patients survived after extracardiac Fontan procedure. Prolonged chest tube drainage (> 7 days) was required in 9 (36%) patients. Follow-up was complete and mean follow-up was 24.6 ± 11.5 months (1-39 months). One patient died 3 months postoperatively. Routine serial postoperative echocardiographic examinations in all patients and magnetic resonance angiography in 6 patients with suspect flow patterns in echocardiography did not reveal any problems with the Fontan circuit. Conclusions: Fresh autologous pericardial tube conduit is a suitable and safe alternative for extracardiac Fontan procedures. Major advantages are availability, no cost, easy handling and hemostasis, low risk of thrombosis and emboli, and growth potential.
Keywords: adolescent; adult; article; blood flow; child; clinical article; controlled study; echocardiography; embolism; female; follow up; Fontan procedure; heart output; hemostasis; human; magnetic resonance angiography; male; oxygen saturation; postoperative complication; postoperative period; postoperative thrombosis; priority journal; risk reduction; safety; surgical technique; survival rate; treatment outcome; tube

Outcomes regarding the central nervous system in children with complex congenital cardiac malformations - Wernovsky, G. (Cardiology in the Young, 2005)
The number of children now surviving surgical interventions because of congenital cardiac disease continues to increase. Indeed, it is estimated that, by the end of 2005, there will be more adults than children with congenital cardiac malformations. The complex challenges facing this growing population are only now becoming apparent, including the continued hazard for mortality, the risk of reoperation, and newly-emerging late sequels of surgery. In particular, children with severe lesions requiring intervention in the neonatal period are surviving at levels thought to be highly improbable no more than two decades ago. Heralded by the availability of prostaglandin E1 in the late 1970s, improvements in technology, such as echocardiography, and color Doppler in particular, intensive care and intraoperative support, have recently allowed surgeons to reconstruct the hearts of many children with otherwise lethal defects. Much of the published literature has focused on the cardiac sequels in this population. Increasing attention has recently been given, nonetheless, to the neurodevelopmental outcomes in this population of patients. © 2005 Cambridge University Press.
Keywords: article; cardiopulmonary bypass; central nervous system disease; child; cognition; congestive heart failure; disease severity; heart arrhythmia; heart surgery; human; hypoplastic left heart syndrome; learning disorder; mortality; perioperative period; postoperative period; reoperation; seizure; cerebrovascular accident; surgical technique; survival

Detection and prevention of neurologic injury in the intensive care unit - Hoffman, G.M. (Cardiology in the Young, 2005)
Survivors of repairs of complex congenital cardiac malformations in infancy have an increased risk of permanent abnormalities in motor, cognitive, expressive, and behavioral functioning. These functional deficits are expressions of complex interactions of environment, including prolonged hospitalization and conditioned child-parental behaviours, alterations of social environment, the effects of physical limitations, biological influences including genetic determinants, prenatal injury, and acquired reversible and irreversible neuronal injury.1,2 The magnitude of the problem is large, with incidence dependent upon the measures used for assessment. Overt postoperative neurologic signs have been recorded in up to one-tenth of postoperative infants and children, with double that rate found in those with abnormalities of the aortic arch.3 A decreased potential for development, based upon parent-sibling models, has been estimated to occur in one-third of survivors.4,5 Evidence of injury is provided by magnetic resonance imaging in up to one-third of patients preoperatively, and between half and nine-tenths postoperatively, although most of these early postoperative changes will disappear.5 Although recent changes in perioperative management are likely to reduce such neurologic injury, their significance remains high. © 2005 Cambridge University Press.
Keywords: protein S100B; aortic arch anomaly; article; brain injury; brain metabolism; brain oxygen consumption; computer assisted tomography; congenital heart malformation; disease severity; echography; electroencephalography; heart surgery; high risk patient; human; hypoplastic left heart syndrome; incidence; induced hypothermia; intensive care; intensive care unit; near infrared spectroscopy; neurologic disease; nuclear magnetic resonance imaging; pathophysiology; patient safety; pediatric surgery; perioperative period; postoperative period; preoperative evaluation; primary prevention; risk factor; risk reduction; surgical risk

Incidence and treatment of diaphragmatic paralysis after cardiac surgery in children - Joho-Arreola, A.L.; Bauersfeld, U.; Stauffer, U.G.; Baenziger, O.; Bernet, V. (European Journal of Cardio-thoracic Surgery, 2005)
Objective: Diaphragmatic paralysis (DP) caused by phrenic nerve injury is potentially life-threatening in infants. Phrenic nerve injury due to thoracic surgery is the most common cause of DP in children. We retrospectively analyzed incidence, surgical details, management and follow-up of our patients with DP after cardiac surgery to develop an algorithm for the management and follow-up. Methods: Retrospective analysis of 43 patients with DP after cardiac surgery performed between 1996 and 2000. Results: Median age at cardiac surgery was 1 month (range 3 days to 9 years). Incidence of DP was 5.4%. A trend towards higher incidences of DP were observed after arterial switch operation (10.8%, P=0.18), Fontan procedure (17.6%, P=0.056) and Blalock-Taussig Shunt (12.8%, P=0.10). Median time from cardiac surgery to surgical plication was 21 days (range 7-210 days). Transthoracic diaphragmatic plication was performed in 29/43 patients, no plication was done in 14/43 patients. Patients in whom diaphragmatic plication was required were younger (median age 2 months, range 21 days to 53 months versus 17.5 months, range 4 days to 110 months; P<0.001). Indications for plication were failure to wean from ventilator (n=22), respiratory distress (n=4), cavopulmonary anastomosis (n=2), and failure to thrive (n=1). All these symptoms resolved after diaphragmatic plication, however, 8/29 patients with plication and 2/14 without plication died. Cause of death was not related to diaphragmatic plication in any patient. Position of plicated diaphragm was normal in 18/21 surviving patients 1 month after plication. In 2/12 surviving patients without plication hemidiaphragm showed a normal position 1 year after surgery. The rate of pulmonary infections was not significantly different during 12-60 months follow-up. Conclusions: DP is an occasional complication of cardiac surgery. High incidences of DP were seen after arterial switch operation, Fontan procedure and Blalock-Taussig shunt (BT). Respiratory insufficiency requires diaphragmatic plication in most infants with DP whereas older children may tolerate DP. Transthoracic diaphragmatic plication is an effective treatment of DP and achieves relief of respiratory insufficiency in most patients. Spontaneous recovery from postsurgical DP is rare. © 2004 Elsevier B.V. All rights reserved.
Keywords: algorithm; analytic method; anastomosis; article; assisted ventilation; cause of death; diaphragm paralysis; follow up; Fontan procedure; heart surgery; human; incidence; priority journal; respiratory distress; shunting; surgical technique; treatment failure; treatment indication

Congenital anomaly surveillance in England - Ascertainment deficiencies in the national system - Boyd, P.A.; Armstrong, B.; Dolk, H.; Botting, B.; Pattenden, S.; Abramsky, L.; Rankin, J.; Vrijheid, M.; Wellesley, D. (British Medical Journal, 2005)
Objective: Firstly, to assess the completeness of ascertainment in the National Congenital Anomaly System (NCAS), the basis for congenital anomaly surveillance in England and Wales, and its variation by defect, geographical area, and socioeconomic deprivation. Secondly, to assess the impact of the lack of data on pregnancies terminated because of fetal anomaly. Design: Comparison of the NCAS with four local congenital anomaly registers in England. Setting: Four regions in England covering some 109 000 annual births. Participants: Cases of congenital anomalies registered in the NCAS (live births and stillbirths) and independently registered in the four local registers (live births, stillbirths, fetal losses from 20 weeks' gestation, and pregnancies terminated after prenatal diagnosis of fetal anomaly). Main outcome measure: The ratio of cases identified by the national register to those in local registry files, calculated for different specified anomalies, for whole registry areas, and for hospital catchment areas within registry boundaries. Results: Ascertainment by the NCAS (compared with data from local registers, from which terminations of pregnancy were removed) was 40% (34% for chromosomal anomalies and 42% for non-chromosomal anomalies) and varied markedly by defect, by local register, and by hospital catchment area, but not by area deprivation. When terminations of pregnancy were included in the register data, ascertainment by NCAS was 27% (19% for chromosomal anomalies and 31% for non-chromosomal anomalies), and the geographical variation was of a similar magnitude. Conclusion: The surveillance of congenital anomalies in England is currently inadequate because ascertainment to the national register is low and non-uniform and because no data exist on termination of pregnancy resulting from prenatal diagnosis of fetal anomaly.
Keywords: article; chromosome aberration; cleft lip; cleft palate; congenital heart malformation; congenital malformation; diaphragm hernia; digestive system malformation; Down syndrome; Fallot tetralogy; fetus; fetus malformation; gastroschisis; health care system; human; hypoplastic left heart syndrome; infant; kidney polycystic disease; limb malformation; major clinical study; national health service; neural tube defect; newborn; pregnancy termination; prenatal diagnosis; priority journal; register; spinal dysraphism; stillbirth; umbilical hernia; United Kingdom

Quality of life in children with pulmonary atresia and intact ventricular septum. - Ekman-Joelsson, B.M.; Berntsson, L.; Sunnegårdh, J. (Cardiology in the young, 2004)
OBJECTIVE: To measure quality of life in children with pulmonary atresia and intact ventricular septum, and make comparisons with a healthy group of children from the general Swedish population. An additional aim was to compare quality of life in two subgroups, children undergoing biventricular and univentricular repair, the latter by establishment of the Fontan circulation. METHODS: Quality of life was measured using a mailed questionnaire, taking into consideration the three spheres of personal, interpersonal, and external living conditions. In all, 52 children received the questionnaire, and the answers were compared with those of a random sample of 1856 healthy Swedish children. RESULTS: We received responses from 42 children and parents. The overall differences between groups were small, and no difference was found when comparing the children undergoing univentricular as opposed to biventricular surgical repair. In terms of personal quality of life, we found a higher level of psychosomatic complaints, and lower satisfaction with their own and parent-child activities, in those with the congenital anomaly than in their normal peers. In terms of the interpersonal sphere, more time was available for those with malformed hearts, but the experience of support from the relatives was significantly lower. CONCLUSIONS: Overall, quality of life was equal between children with pulmonary atresia and intact ventricular septum and the children in the reference group. The personal psychological conditions were less favourable for children with pulmonary atresia and intact ventricular septum. The perceived lack of support from relatives was also higher in these families. No difference was found when comparing the children undergoing univentricular and biventricular surgical repair.
Keywords: adolescent; adult; article; child; comparative study; heart septum defect; human; infant; pulmonary valve atresia; preschool child; psychological aspect; quality of life; questionnaire

Proximity of residence to trichloroethylene-emitting sites and increased risk of offspring congenital heart defects among older women - Yauck, J.S.; Malloy, M.E.; Blair, K.; Simpson, P.M.; McCarver, D.G. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2004)
BACKGROUND: Previous studies suggest that trichloroethylene (TCE) is a selective cardiac teratogen. We tested the hypothesis that the odds of maternal residence close to TCE-emitting sites would be greater among infants with congenital heart defects (CHDs) than among infants without CHDs. METHODS: We conducted a case-control study of 4025 infants, identified from hospital and birth records, born from 1997 to 1999 to Milwaukee, Wisconsin mothers. A geographic information system was used to calculate distances between maternal residences and TCE sites. We used classification tree analysis to determine appropriate values by which to dichotomously categorize mothers by TCE exposure (exposed: residence within 1.32 miles of at least one TCE site) and age (older: ≥38 years), and logistic regression to test for CHD risk factors. RESULTS: The proportion of mothers who were both older and had presumed TCE exposure was more than six-fold greater among case infants than among control infants (3.3% [8/245] versus 0.5% [19/3780]). When adjusted for other variables, CHD risk was over three-fold greater among infants of older, exposed mothers compared to infants of older, nonexposed mothers (adjusted OR, 3.2; 95% CI, 1.2-8.7). Older maternal age, alcohol use, chronic hypertension, and preexisting diabetes were each associated with CHDs (adjusted ORs, 1.9, 2.1, 2.8, 4.1; 95% CIs, 1.1-3.5, 1.1-4.2, 1.2-6.7, 1.5-11.2, respectively), but residence close to TCE sites alone was not. CONCLUSIONS: Our findings suggest that maternal age and TCE exposure interact to increase CHD risk, although the mechanism by which this occurs is unknown. A prospective study is underway to confirm this finding. © 2004 Wiley-Liss, Inc.
Keywords: teratogenic agent; trichloroethylene; adult; age; alcohol consumption; aortic coarctation; article; chronic disease; congenital heart malformation; controlled study; diabetes mellitus; disease association; Ebstein anomaly; environmental exposure; Fallot tetralogy; great vessels transposition; heart atrium septum defect; heart ventricle septum defect; human; hypertension; hypoplastic left heart syndrome; infant; pulmonary valve atresia; major clinical study; maternal age; mitral valve atresia; mitral valve stenosis; priority journal; progeny; pulmonary valve stenosis; residential home; risk assessment; risk factor; tricuspid valve atresia

Prevention of early sudden circulatory collapse after the norwood operation - De Oliveira, N.C.; Ashburn, D.A.; Khalid, F.; Burkhart, H.M.; Adatia, I.T.; Holtby, H.M.; Williams, W.G.; Van Arsdell, G.S. (Circulation, 2004)
Background-After modifications in our perioperative management protocol, we have observed a decrease in sudden circulatory collapse after the Norwood operation. The current study examines early outcomes after the Norwood operation in our unit in an attempt to identify variables that may have altered the risk of unexpected circulatory collapse. Methods and Results-We studied 105 consecutive neonates who underwent a Norwood operation in our institution. Our treatment protocol has changed in the past 3 years to include the use of alpha-blockade with phenoxybenzamine (POB) for systemic afterload reduction and selective cerebral perfusion. Forty-eight infants had selective cerebral perfusion. Forty-two infants received POB. Sixty patients had hypoplastic left heart syndrome. There was no difference in age, diagnosis, number of neonates with weight <2.5 kg, aortic size diameter <2 mm, highest preoperative lactate level, and shunt size indexed to body weight among patients with or without use of POB. Twenty-five infants had circulatory collapse during the first 72 hours. Twelve of them could be explained by technical issues. Thirteen others who appeared clinically stable had early sudden circulatory collapse without an apparent cause. Sixteen out of 25 neonates died. Of those with technical problems, 8 out of 12 died. Based on the hazard function, 3 incremental risk factors for early circulatory collapse were technical issue at operation (P<0.001), longer cross-clamp time (P<0.007), and no use of POB (P<0.002). For a technically successful operation, freedom from circulatory collapse at 72 hours is 95% with the use of POB versus 69% without (P<0.002). Diagnosis, aortic size, atrioventricular valve function, birth weight, age at operation, and total circulatory arrest time and were not predictive of early sudden circulatory collapse. Conclusion-Recent changes in our treatment protocol have resulted in a decrease incidence of sudden circulatory collapse after the Norwood operation. Optimal surgical technique is the most important predictor of early survival. The use of aggressive afterload reduction with POB reduced the risk of early sudden arrest.
Keywords: alpha adrenergic receptor blocking agent; phenoxybenzamine; article; body weight; brain perfusion; cardiovascular risk; circulation; clinical protocol; controlled study; correlation analysis; disease association; female; heart afterload; heart death; human; hypoplastic left heart syndrome; infant; major clinical study; male; newborn; Norwood procedure; outcomes research; patient satisfaction; patient selection; postoperative complication; prediction; preoperative care; priority journal; shock; surgical technique; treatment outcome

Hypoplasia of the small pulmonary arteries in hypoplastic left heart syndrome with restrictive atrial septal defect - Maeda, K.; Yamaki, S.; Kado, H.; Asou, T.; Murakami, A.; Takamoto, S. (Circulation, 2004)
Background-Restrictive atrial septal defect (ASD) (including intact atrial septum [LAS]) has been reported to be a risk factor that negatively impacts survival in hypoplastic left heart syndrome (HLHS). Although lymphangiectasia and "arterialization" of the veins of the lung in HLHS with restrictive ASD have been reported, they cannot fully explain the high mortality. We have introduced a new method of evaluating the development of the pulmonary vasculature in histological sections and used it to assess patients' lungs. We tested the hypothesis that the small pulmonary arteries (SPA), which are pulmonary arteries in a histological section whose radii are ≈25 μm to 250 μm, in HLHS with restrictive ASD are hypoplastic, but that the alveoli are not, to elucidate the mechanism underlying the poor outcome of these patients. Methods and Results-Fourteen HLHS patients between 1 day and 40 days of age were studied. In 8 cases, the ASD was restrictive [R(+) group], and in the other 6 cases it was not [R(-) group]. Specimens from 12 autopsies of cases with no congenital heart or pulmonary disease were examined as a control group (C group). As a novel histological parameter, we assessed the size of SPA in relation to the size of accompanying bronchioles to identify SPA underdevelopment. To evaluate the development of alveoli and interstitial tissue, radial alveolar counts (RAC), which reflect alveolar maturity and complexity, were also performed. Statistical comparisons between groups were made by analysis of covariance with age as a covariant factor. When the radius of the accompanying bronchiole was 100 μm, the radius of the SPA was 34.0±10.8 μm in the R(+) group, and significantly lower than the 46.6±8.5 μm in R(-) group (P=0.0022) and 70.5±8.4 μm in the C group (P<0.0001). The RAC was in 3.5±0.9 in the R(+) group, 3.4±0.6 in the R(-) group, and 3.7±0.9 in the C group (no significant differences between groups). Conclusion-The SPA in HLHS with restrictive ASD were underdeveloped compared with the SPA in HLHS with nonrestrictive ASD and the controls, but their alveoli were not hypoplastic. Based on these results, it is speculated that SPA hypoplasia may be responsible for the poor outcome of HLHS with restrictive ASD.
Keywords: analysis of variance; artery dysplasia; article; autopsy; bronchiole; clinical article; congenital heart disease; controlled study; correlation analysis; female; heart atrium septum defect; human; human tissue; hypoplastic left heart syndrome; infant; intermethod comparison; interstitium; lung artery hypoplasia; lung disease; male; medical assessment; newborn; outcomes research; pathogenesis; patient satisfaction; postoperative complication; priority journal; restrictive cardiomyopathy; statistical significance; surgical technique

Neuropsychological outcome of infant heart transplant recipients - Baum, M.; Catherin Freier, M.; Freeman, K.; Babikian, T.; Ashwal, S.; Chinnock, R.; Bailey, L. (Journal of Pediatrics, 2004)
To assess long-term neuropsychological outcomes of infant heart transplant recipients.Fifty-five children (mean age, 6.4 years) with a primary diagnosis of hypoplastic left heart syndrome or other cardiac disorders participated in the study. Six areas of risk were assessed (birth; preoperative, intraoperative, and postoperative status; long-term medical complications; and socioeconomic factors). Neuropsychological evaluations included the following: Wechsler Scales of Intelligence, Wechsler Individual Achievement Test, Berry Visual Motor Integration Scale, Comprehensive Evaluation of Language Function, and Achenbach Child Behavioral Checklist.Intellectual functioning scores revealed a mean full-scale IQ of 81 ± 19. Intraoperative and postoperative variables (bypass time, hospital course, and lowest posttransplant pH), long-term medical complications (serious infections and posttransplant surgical procedures), and socioeconomic factors were associated with cognitive functioning. Visual-motor functioning was also related to bypass and total support time.Long-term outcomes reveal low-average neuropsychological functioning and are related to intrasurgical-postsurgical, long-term medical, and socioeconomic factors. The neuropsychological and psychosocial functioning of infant heart transplant recipients will be important to address as they mature during adolescence and adulthood.
Keywords: article; bypass surgery; child; cognition; controlled study; female; heart disease; heart graft; human; hypoplastic left heart syndrome; infant; infection complication; long term care; major clinical study; male; maturation; neurologic examination; neuropsychology; postoperative complication; postoperative infection; priority journal; risk assessment; socioeconomics; treatment outcome; visuomotor coordination

Assessment of physician directiveness: Using hypoplastic left heart syndrome as a model - Kon, A.A. (Journal of Perinatology, 2004)
Objective: To test the hypothesis that surgeons are more directive than pediatricians in discussions with parents of critically ill children. Study Design: We designed a novel tool to assess physician directiveness in discussions with parents of children with hypoplastic left heart syndrome. We sent surveys containing the assessment tool as well as demographic questions to all attending physicians in Neonatology, Pediatric Critical Care, Pediatric Cardiology, and Congenital Cardiac Surgery at 14 of the largest pediatric cardiac surgery centers in the United States. Responses to the tool were used to determine a "directiveness score" for each physician. We then performed univariate and multivariable linear regression analyses to assess the association of physician specialty, race/ethnicity, religion, gender, and years in practice with the directiveness score. Results: Responses from 138 physicians were analyzed. In univariate analyses, with neonatologists as the reference group, surgeons were most directive (regression coefficient 3.02, 95% confidence interval 0.69 to 5.35, P=0.01), followed by cardiologists (regression coefficient 1.67, 95% confidence interval 0.13 to 3.20, P=0.03). No other variable was associated with physician directiveness score. These results were similar in the multivariable analysis. Conclusions: These results suggest that physician specialty is associated with directiveness. It is unclear, however, what amount of direction parents of critically ill children prefer. © 2004 Nature Publishing Group. All rights reserved.
Keywords: article; controlled study; critical illness; demography; ethnology; female; gender; human; hypoplastic left heart syndrome; linear regression analysis; male; medical practice; parent; parent counseling; pediatrician; physician attitude; race; religion; scoring system; surgeon; United States

Neurodevelopmental outcomes in hypoplastic left heart syndrome - Mahle, W.T.; Wernovsky, G. (Pediatric Cardiac Surgery Annual, 2004)
Infants with hypoplastic left heart syndrome (HLHS) are now surviving to school age and early adulthood because of surgical palliation with either staged reconstruction or transplantation. Although in some respects these patients are doing remarkably well, recent investigations have shown that they are at risk for cognitive, neuromotor, and psychosocial problems. This article examines the neurodevelopmental outcome for children and adolescents with HLHS. In addition, hemodynamic and genetic factors unique to this patient population that may impact longer-term outcome are explored. The continued evolution of the pre-, intra- and post-operative care of the patient with HLHS has significantly improved early survival. Concomitant changes in care, such as selective cerebral perfusion and neurologic monitoring, aimed at reducing neurologic insult may also favorably impact later neurodevelopmental status. © 2004 Elsevier Inc. All rights reserved.
Keywords: adolescent; article; brain perfusion; cognition; heart hemodynamics; heart surgery; heart transplantation; heredity; human; hypoplastic left heart syndrome; long term care; motoneuron; neurologic examination; patient monitoring; postoperative care; risk factor; school child; social psychology; surgical technique; survival; treatment outcome

Total cavopulmonary connection to one lung - Jacobs, M.L.; Schneider, D.J.; Pourmoghadam, K.K.; Pizarro, C.; Norwood, W.I. (Pediatric Cardiac Surgery Annual, 2004)
The status of pulmonary circulation is of utmost importance to the success of the modified Fontan operation. Pulmonary artery distortion, hypoplasia of the total pulmonary vascular bed, and elevated pulmonary vascular resistance are all risk factors for adverse outcome after modified Fontan operations. In cases of irreparable acquired atresia of one or the other branch pulmonary artery, clinicians are forced to contemplate the possibility of total cavopulmonary connection to one lung. The combined experience of the authors with 12 cases suggests that the likelihood of operative survival following Fontan's operation to one lung is predicted based on the usual hemodynamic parameters: pulmonary artery pressure and flow, ventricular end diastolic pressure, transpulmonary gradient, and pulmonary vascular resistance. In this series, there were no operative mortalities among patients undergoing Fontan's operation to one lung, all of whom meet the usual criteria for hemodynamic acceptability. There may, however, be a higher incidence of protein-losing enteropathy than in Fontan patients with normal pulmonary vascular beds. All possible means of resuscitating the lost elements of the pulmonary vascular bed and re-establishing pulmonary artery continuity should be attempted to minimize pulmonary vascular capacitance of patients undergoing Fontan's operation. It is clear, however, that the presence of only one pulmonary artery does not in and of itself preclude satisfactory outcome. © 2004 Elsevier Inc. All rights reserved.
Keywords: acetylsalicylic acid; captopril; digoxin; enalapril; furosemide; octreotide; oxygen; prednisone; spironolactone; article; child; Fontan procedure; heart ventricle enddiastolic pressure; hemodynamic parameters; human; hypoplastic left heart syndrome; lung artery pressure; lung blood flow; lung circulation; lung hypoplasia; lung vascular resistance; patient satisfaction; pulmonary valve atresia; risk factor; surgical mortality; survival; treatment outcome; tricuspid valve atresia; aspirin; lasix

Long-term outcome and quality of life in adult patients after the Fontan operation - Van Den Bosch, A.E.; Roos-Hesselink, J.W.; Van Domburg, R.; Bogers, A.J.J.C.; Simoons, M.L.; Meijboom, F.J. (American Journal of Cardiology, 2004)
The first successful Fontan operation was performed in 1971, and this first cohort of Fontan patients is reaching adulthood with unclear outcome of this palliative procedure. We studied the mortality, morbidity, and quality of life in our adult Fontan patients. We examined all patients (n = 36) who underwent a Fontan procedure and were being seen in an adult outpatient clinic by using electrocardiography, exercise testing, and echocardiography. Quality of life was assessed by the Short Form 36 questionnaire. The mean follow-up period was 15 years (range 0 to 23). Of the initial 36 patients, 10 died (28%) at a mean of 10 years (range 0 to 21) after the Fontan operation and 1 patient underwent cardiac transplantation. Reoperations were performed in 21 patients (58%), and the most common reason was revision of the Fontan connection. Sustained supraventricular tachycardia was observed in 20 patients (56%) with an increased incidence of arrhythmias with longer follow-up. Thromboembolic events were detected in 9 patients (25%), 5 of whom had adequate anticoagulant levels at the time of event. The thromboembolic event was fatal for 3 patients. A total of 195 hospital admissions (mean 3.8 ± 2.7, range 1 to 13) was recorded. Quality-of-life assessment showed physical functioning, mental health, and general health perception to be significantly lower for Fontan patients than for the normal Dutch population. Thus, we found high mortality and very high morbidity in adult patients after the Fontan operation. In particular, reoperations, arrhythmias, and thromboembolic events compromised quality of life. © 2004 by Excerpta Medica, Inc.
Keywords: adolescent; adult; article; child; clinical article; electrocardiography; follow up; Fontan procedure; heart arrhythmia; heart transplantation; hospital admission; human; medical assessment; medical record; mental health; morbidity; mortality; outpatient; priority journal; quality of life; reoperation; supraventricular tachycardia; thrombosis

Cardiac transplantation for hypoplastic left heart syndrome. - Boucek Jr., R.J.; Chrisant, M.R. (Cardiology in the young, 2004)
Future improvements can be expected in cardiac transplantation in children. We continue to advance our understanding of the immune system, and to develop more specific immunosuppressive agents. Ultimately, the future for recipients may be improved by strategies such as induction therapy or donor-derived chimeric destined transfusions, designed to enhance the tolerance of the host to a human leukocyte antigen incompatible graft. Improvements in tolerance of the host would allow for reduction or elimination of many, if not all, of the immunosuppressive agents, and for longevity extending well into the adulthood. Survival, particularly for infants, has improved dramatically in the last decade. The most recent results from the registry of the International Society of Heart and Lung Transplantation/United Network for Organ Sharing show that recipients less than one year old at transplantation, who survive the first year, have greater than a 95% survival to four years (Fig. 1). As late outcomes continue to improve, transplantation will provide a better quality and duration of life for infants with hypoplastic left heart syndrome. It is possible, nonetheless, that some infants will require retransplantation, since the half life of a transplanted heart in children has been about 12 years. The alternative is conventional surgery with multiple palliative operations, and the need for later transplantation as end-stage cardiac function is reached. Efforts to increase potential donors and donor utilization can be supported by innovative schemes, such as ABO incompatible transplants. Additional efforts are made more urgent when the current data indicate excellent outcomes after transplantation, but a high mortality while waiting for transplantation.
Keywords: article; child; child development; heart transplantation; human; hypoplastic left heart syndrome; infant; kidney function test; mortality; newborn; quality of life; survival; survival rate; time; treatment outcome

Routine mechanical ventricular assist following the Norwood procedure - Improved neurologic outcome and excellent hospital survival - Ungerleider, R.M.; Shen, I.; Yeh Jr., T.; Schultz, J.; Butler, R.; Silberbach, M.; Giacomuzzi, C.; Heller, E.; Studenberg, L.; Mejak, B.; You, J.; Farrel, D.; et al. (Annals of Thoracic Surgery, 2004)
Background. Although excellent survival following the Norwood procedure for palliation of hypoplastic left heart syndrome (HLHS) is being achieved by some, most centers, especially the ones with small surgical volume and limited experience, continue to struggle with initial results. Survivors often showed evidence of significant neurologic injury. The early postoperative care is labor-intensive as attempts are made to balance the systemic and pulmonary circulation for these infants. We report our experience with routine use of mechanical circulatory assist to support the increased cardiac output requirements present following Norwood procedure. Methods. Eighteen consecutive infants undergoing Norwood operation for HLHS (Oregon Health & Science University [OHSU] 13; University of Louisville [UL] 5) were placed on a ventricular assist device (VAD) immediately following modified ultrafiltration in the operating room using the cardiopulmonary bypass (CPB) cannulas that were in the right atrium and the neoaorta. VAD flows were maintained at approximately 200 mL·kg-1·min-1 and the patients were transported to the intensive care unit (ICU). Patients operated at OHSU also received neurodevelopmental testing before their Glenn procedure, approximately 4 to 6 months following their Norwood operation. Results. All patients were stable on VAD support and no attempt was made to balance the systemic and pulmonary circulation. The ventilator was manipulated to achieve systemic Pa02 between 30 and 45 mm Hg and PaC02 between 35 and 45 mm Hg. Evidence of hypoperfusion (increasing lactates) was managed by increasing the VAD flow. Lactates normalized [< 2 mmol/L]) by 1.8 ± 1.1 days following surgery. Average time of VAD support was 3.1 ± 1.0 (range, 2 to 5 days) and average time until chest closure was 3.4 ± 1.5 (range, 2 to 8 days). There were two cases of postoperative bleeding (11.1%) requiring reexploration and one case of mediastinitis (5.5%) in a patient who has now gone on to successful Glenn. Sixteen of the eighteen patients survived (hospital survival mean 89% with a 95% confidence interval of 63.9% to 98.1%; 12/13 OHSU [92.3%]; 4/5 UL [80%]). Neurodevelopmental testing using the Mullen Scales of Early Learning and the Vineland Adaptive Behavior Scale were normal for all infants tested. Conclusions. Routine postoperative use of VAD can support the increased cardiac output demands of infants following Norwood operation and results in a stable postoperative convalescence that does not require aggressive ventilator or inotrope manipulation. Although not a panacea, this strategy can simplify postoperative management, lead to excellent hospital survival, and possibly augment cerebral oxygen delivery, resulting in improved neurologic outcomes for this challenging group of patients. © 2004 by The Society of Thoracic Surgeons.
Keywords: lactic acid derivative; aorta; arterial carbon dioxide tension; article; assisted circulation; blood flow; cannula; cardiopulmonary bypass; child behavior; clinical article; confidence interval; controlled study; follow up; heart assist device; heart output; heart right atrium; hemodynamic monitoring; hospital; human; hypoplastic left heart syndrome; infant; intensive care; lung circulation; mediastinitis; neurologic examination; neurology; operating room; oxygen tension; perfusion; postoperative care; postoperative hemorrhage; priority journal; statistical significance; surgical patient; survival rate; systemic circulation; treatment outcome; ultrafiltration; United States; ventilator

Global impairment of cardiac autonomic nervous activity late after the Fontan operation - Davos, C.H.; Francis, D.P.; Leenarts, M.F.E.; Yap, S.-C.; Li, W.; Davlouros, P.A.; Wensel, R.; Coats, A.J.S.; Piepoli, M.; Sreeram, N.; Gatzoulis, M.A. (Circulation, 2003)
Background - Atrial tachyarrhythmia is a common cause of morbidity and mortality in patients with univentricular physiology undergoing the Fontan operation. We examined cardiac autonomic nervous activity, a predictor of arrhythmia and sudden death in other cardiovascular disease, in patients late after the Fontan operation, employing heart rate variability (HRV) and baroreflex sensitivity. Methods and Results - We measured HRV and baroreflex sensitivity in 22 consecutive patients (8 male, age 26±9 years) who had undergone the Fontan operation 13±6 years previously, and 22 age- and sex-matched healthy controls. Fontan patients had significantly lower HRV (P<0.0001). Baroreflex sensitivity was measured by the α-index method (square root of ratio of RR interval spectral power to systolic blood pressure (SBP) spectral power, in the LF and the HF band) and was also significantly depressed in the Fontan group (P<0.0001 for both). Both low frequency (LF) and high frequency (HF) components of HRV were reduced in the Fontan patients (P<0.0001), but there was interindividual variation so that the LF/(LF+HF) ratio may be high, normal, or low, and decreased with increasing right atrial dimensions (r=-0.62, P=0.006). Patients with a history of sustained atrial arrhythmia had a stronger baroreflex than those without (P=0.005). Conclusions - Autonomic nervous control of the heart is markedly deranged in patients late after the Fontan operation, with reduced HRV and baroreflex sensitivity. A relative suppression of the sympathetic-compared with the parasympathetic-system was observed in patients with marked right atrial dilation within the Fontan group. Furthermore, stronger baroreflexes were seen in Fontan patients in association with a higher incidence of sustained atrial tachyarrhythmia, implying that sinus node dysfunction is unlikely to be the dominant mechanism. Additional studies are clearly required to examine the prognostic importance of impaired BRS and HRV in these patients.
Keywords: adolescent; adult; article; autonomic dysfunction; cardiovascular disease; cholinergic activity; clinical article; controlled study; correlation analysis; female; Fontan procedure; heart atrium enlargement; heart rate variability; heart right atrium; heart single ventricle; heart size; human; male; measurement; prediction; pressoreceptor reflex; priority journal; prognosis; RR interval; sinus node disease; sudden death; supraventricular tachycardia; sympathetic tone; systolic blood pressure; procedures

Electrocardiographic ST segment depression and clinical function in children with Fontan circulation - Rydberg, A.; Rask, P.; Teien, D.E.; Hörnsten, R. (Pediatric Cardiology, 2003)
Previous studies noted that Fontan patients have electrocardiographic ST depressions during exercise tests and on 24-hour ambulatory electrocardiographic (ECG) monitoring. This study investigated whether the ST depressions were correlated to clinical function (NYHA Functional Classification). Forty-five children in two groups were examined - 15 patients with Fontan circulation and 30 with a structurally normal heart, matched for sex, height, and weight. Clinical and echocardiographic examinations were performed. The clinical state was defined as NYHA functional classes I-IV. All 45 children underwent 24-hour ECG and an analysis of ST changes was performed, with ST segment depression >0.20 mV at ST 60 regarded as significant. Twelve of 15 patients had significant 24-hour ECG ST depressions; in 9 of 12 patients these occurred on more than one occasion. Comparing 24-hour ECG recordings from patients in NYHA I with patients in NYHA II or III showed a significant difference in depth (p = 0.0023), duration (p = 0.0016), and number of ST depressions (p = 0.0001). None of the matched healthy children showed ST depressions. Repeated ST analysis on 24-hour ECG shows that the ST depressions seem to be correlated to functional status and this may be a useful tool in clinical praxis.
Keywords: digoxin; adolescent; ambulatory monitoring; article; child; clinical article; comparative study; congenital heart disease; controlled study; correlation analysis; daily life activity; diagnostic procedure; diagnostic value; disease classification; electrocardiography; exercise test; female; Fontan procedure; heart ventricle function; human; male; ST segment depression; statistical significance; Danica Holter Replay Unit; Sherpa recorder; Tracker II

Basal pulmonary vascular resistance and nitric oxide responsiveness late after fontan-type operation - Khambadkone, S.; Li, J.; De Leval, M.R.; Cullen, S.; Deanfield, J.E.; Redington, A.N. (Circulation, 2003)
Background - The pulsatile nature of pulmonary blood flow is important for shear stress-mediated release of endothelium-derived nitric oxide (NO) and lowering pulmonary vascular resistance (PVR) by passive recruitment of capillaries. Normal pulsatile flow is lost or markedly attenuated after Fontan-type operations, but to date, there are no data on basal pulmonary vascular resistance and its responsiveness to exogenous NO at late follow-up in these patients. Methods and Results - We measured indexed PVR (PVRI) using Fick principle to calculate pulmonary blood flow, with respiratory mass spectrometry to measure oxygen consumption, in 15 patients (median age, 12 years; range, 7 to 17 years; 12 male, 3 female) at a median of 9 years after a Fontan-type operation (6 atriopulmonary connections, 7 lateral tunnels, 2 extracardiac conduits). The basal PVRI was 2.11±0.79 Wood unit (WU) times m2 (mean±SD) and showed a significant reduction to 1.61±0.48 (P=0.016) after 20 ppm of NO for 10 minutes. The patients with nonpulsatile group in the pulmonary circulation dropped the PVRI from 2.18±0.34 to 1.82±0.55 (P<0.05) after NO inhalation. Conclusions - PVR falls with exogenous NO late after Fontan-type operation. These data suggest pulmonary endothelial dysfunction, related in some part to lack of pulsatility in the pulmonary circulation because of altered flow characteristics. Therapeutic strategies to enhance pulmonary endothelial NO release may have a role in these patients.
Keywords: nitric oxide; oxygen; adolescent; article; calculation; clinical article; clinical protocol; endothelium; female; Fontan procedure; human; lung blood flow; lung circulation; lung vascular resistance; male; mass spectrometry; oxygen consumption; priority journal; school child

Myocardial perfusion and coronary flow reserve assessed by positron emission tomography in patients after Fontan-like operations - Hauser, M.; Bengel, F.M.; Kühn, A.; Sauer, U.; Nekolla, S.G.; Eicken, A.; Schwaiger, M.; Hess, J. (Pediatric Cardiology, 2003)
Ventricular dysfunction in patients after Fontan-like operations (FLOs) is a serious complication that might contribute to poor long-term results. Ischemic heart disease will have debilitating consequences on a Fontan heart. Ten patients (15.8 ± 5.01 years) after FLO had transesophageal echocardiography and cardiac catheterization 9.3 ± 4.2 years after surgery. Myocardial perfusion was assessed by NH3-positron emission tomography (rest/adenosine) and compared with that of 10 healthy adults (26.1 ± 6.3 years). Ventricular function was normal in 4 and reduced in 6 patients; end systolic and end diastolic meridional wall stress was significantly elevated in the FLO group. Coronary angiography revealed no stenosis of the coronaries. Compared to normals, myocardial blood flow (MBF) at rest was higher in the FLO group (0.99 ± 0.25 vs 0.77 ± 0.17 ml/g/min, p < 0.05), whereas MBF after vasodilatation (2.12 ± 0.78 vs 3.10 ± 0.85 ml/g/min, p < 0.05) and coronary flow reserve (CFR) was reduced (2.5 ± 0.88 vs 4.1 ± 1.01, p < 0.05), especially in those with impaired ventricular function. Coronary vascular resistance after vasodilatation was elevated in the FLO group (38.2 ± 17.4 vs 24.5 ± 8.3 mmHg/ml/g/min, p < 0.05). Altered MBF, increased meridional wall stress, and impaired CFR are common findings in FLO. Attenuated CFR and reduced ventricular function are significantly correlated and may be risk factors for the long-term outcome.
Keywords: adolescent; adult; angiocardiography; article; child; clinical article; coronary artery blood flow; coronary artery disease; coronary vascular resistance; diagnostic imaging; female; Fontan procedure; heart catheterization; heart left ventricle function; heart left ventricle mass; heart muscle perfusion; heart ventricle performance; human; ischemic heart disease; male; microcirculation; muscle mass; positron emission tomography; risk assessment; transesophageal echocardiography

Choices physicians would make if they were the parents of a child with hypoplastic left heart syndrome - Kon, A.A.; Ackerson, L.; Lo, B. (American Journal of Cardiology, 2003)
Keywords: article; controlled study; diagnostic value; heart volume; human; hypoplastic left heart syndrome; intensive care; male; mother child relation; neonatology; patient care; physician; postoperative period; pregnancy termination; priority journal; statistical analysis; survival rate; treatment outcome

The modified Fontan procedure: Early and late results in 132 adult patients - Burkhart, H.M.; Dearani, J.A.; Mair, D.D.; Warnes, C.A.; Rowland, C.C.; Schaff, H.V.; Puga, F.J.; Danielson, G.K.; Spray, T.; Drinkwater, D. (Journal of Thoracic and Cardiovascular Surgery, 2003)
Objective: The modified Fontan procedure, usually performed in children, is used for the treatment of anomalies with a single functional ventricle. We reviewed our experience with the modified Fontan procedure performed in the adult patient. Methods: Between October 1973 and May 2001, the modified Fontan procedure was performed on 132 adult patients (74 men, 58 women). Median age was 23 years (range, 18 to 53 years). Diagnoses included tricuspid atresia in 34 patients (26%), double-inlet left ventricle in 48 (36%), and complex lesions in 50 (38%). The majority of patients (89%) had at least one prior palliative procedure; the most common procedures were Blalock-Taussig shunt in 85 patients and Glenn anastomosis in 31. Results: Operations included an atriopulmonary connection in 74 patients, lateral tunnel in 27, intra-atrial conduit in 14, right atrium-to-right ventricle in 9, extracardiac conduit in 3, and other in 5. Overall early mortality was 8.3%. Mortality was 6.5% for operations performed after 1980. This is comparable to the mortality of the modified Fontan procedure performed in children during the same time interval at our institution. All 7 of the early deaths since 1980 occurred in the complex lesion group. Morbidity included prolonged pleural effusion in 36 patients, atrial arrhythmias in 25, reoperation for bleeding in 13, permanent pacemaker in 8, and stroke in 2. Mean follow-up was 9.1 years with a maximum of 21.2 years. Actuarial survival for early survivors was 89% (84,95), 75% (67,84), and 68% (58,79) at 5, 10, and 15 years, respectively. Freedom from late reoperation was 89% (83,95), 85% (78,93), and 80% (70,91) at 5, 10 and 15 years, respectively. The majority (90%) of present survivors were New York Heart Association class I or II at follow-up. Conclusions: In properly selected adult patients with functional single ventricle, the modified Fontan procedure can be performed with early mortality similar to younger patients. Early mortality is more likely with complex lesions. The majority of late survivors have a good quality of life.
Keywords: adult; article; artificial heart pacemaker; Blalock Taussig shunt; bleeding; cardiopulmonary bypass; female; follow up; Fontan procedure; Glenn shunt; heart atrium arrhythmia; heart single ventricle; human; major clinical study; male; mortality; palliative therapy; pleura effusion; priority journal; quality of life; reoperation; cerebrovascular accident; surgical technique; survival; tricuspid valve atresia

Plastic bronchitis: An unusual bronchoscopic challenge associated with congenital heart disease repair - Ishman, S.; Book, D.T.; Conley, S.F.; Kerschner, J.E. (International Journal of Pediatric Otorhinolaryngology, 2003)
Plastic bronchitis is a rare disorder characterized by the formation of branching mucoid bronchial casts. Several pathophysiologic conditions are associated with development of these intrabronchial casts, including congenital heart defects. The management of plastic bronchitis presents an unusual and interesting bronchoscopic challenge. We describe a patient who underwent a Fontan procedure for correction of a congenital heart defect and subsequently developed respiratory distress secondary to plastic bronchitis on two occasions. In both cases, endoscopic intervention was required to remove these casts. A review of the literature, including the proposed etiologies, diagnosis, and current medical and surgical management, is also undertaken. © 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: article; bronchitis; bronchoscopy; case report; clinical trial; congenital heart malformation; controlled clinical trial; controlled study; croupous bronchitis; disease association; disease course; endoscopy; human; male; medical literature; preschool child; priority journal; respiratory distress; surgical technique

The epidemiology of cardiovascular defects, Part 2: A study based on data from three large registries of congenital malformations - Harris, J.A.; Francannet, C.; Pradat, P.; Robert, E. (Pediatric Cardiology, 2003)
There were three objectives of this study: to investigate possible specificity in the association between specific cardiac defects and chromosomal anomalies; to evaluate ways of categorizing cardiac defects into larger groups with epidemiological similarities that could indicate similarities in etiology or pathogenesis; and to analyze the relationship between specific cardiac defects and diabetes. We pooled data on infants (aged 1 year or younger) with congenital cardiovascular defects from three large birth defect registries in California, Sweden, and France. The registries in Sweden and France obtained data through reporting from various sources; in California, medical records were reviewed. For severe congenital heart defects, the percentage of infants with identified chromosomal anomalies varied between 0.9% for d-TGV to 68.4% for ECD. In general, specific cardiac conditions have different risk factors. For example, conotruncal defects have been traditionally grouped, but the data presented in this paper indicates more differences for risk factors for the components of conotruncal defects: tetralogy of Fallot, d-TGV, common truncus, and DORV. In general, we suggest the strategy of "splitting" rather than "lumping" when searching for specific genetic factors and/or teratogens. Adequate analysis thus requires large registries or collaboration among registries. The findings did not support constellations between mothers' diabetes and specific defects.
Keywords: aortic coarctation; aortic valve stenosis; article; congenital malformation; cardiovascular malformation; chromosome aberration; congenital malformation; diabetes mellitus; disease association; disease classification; Down syndrome; Edwards syndrome; endocardial cushion defect; Fallot tetralogy; female; France; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; heredity; human; hypoplastic left heart syndrome; infant; Klinefelter syndrome; pulmonary valve atresia; lung vein drainage anomaly; major clinical study; male; trisomy 13; pulmonary valve stenosis; risk factor; Sweden; teratogenesis; tricuspid valve atresia; triploidy; trisomy 13; trisomy 18; Turner syndrome; United States

Population-based study of L-transposition of the great arteries: Possible associations with environmental factors - Kuehl, K.S.; Loffredo, C.A. (Birth Defects Research Part A - Clinical and Molecular Teratology, 2003)
BACKGROUND: L transposition of the great arteries (l-tga) is an uncommon congenital cardiovascular malformation that occurs from abnormal looping of the primitive cardiac tube. Little is known about risk factors for the development of l-tga. METHODS: This study is a case-control study of 36 cases of l-tga compared to 3,495 population-based live born infant controls in the Baltimore Washington Infant Study (1981-1989 births). Extensive personal and occupational exposure data from parental interviews were available for all subjects. A geographic information system was used to identify potential environmental exposures, for example, hazardous waste sites prioritized for cleanup (National Priority List sites). Adjusted odds ratios (OR) and 95% confidence intervals (CI) were calculated using exact parameter estimates from logistic regression. RESULTS: Most infants with l-tga had multiple cardiovascular anomalies, with single ventricle in 47%. Over 75% of all cases of l-tga occur in two regions of contiguous cases. Within these regions, the case control OR of l-tga are 13.4 (95%CI, 4.7-37.8) Both areas are characterized by release of toxic chemicals into air and by hazardous waste sites. Parental exposures to hair dye, smoking and laboratory chemicals are also associated with case status. CONCLUSIONS: L-tga, a congenital cardiovascular malformation due to very early abnormalities in embryogenesis, is associated strongly with residency in two small regions of Maryland and District of Columbia (DC), and with other parental personal or occupational exposures. Additional research is needed to identify the components of spatial and other associations that constitute etiologic risk factors. © 2003 Wiley-Liss, Inc.
Keywords: chemical compound; hair dye; article; calculation; case control study; confidence interval; controlled study; disease association; embryo development; environmental exposure; environmental factor; geographic information system; geography; great vessels transposition; hazardous waste; human; infant; interview; logistic regression analysis; major clinical study; occupational exposure; population research; priority journal; risk assessment; risk factor; smoking; United States

Late follow-up of 1095 patients undergoing operation for complex congenital heart disease utilizing pulmonary ventricle to pulmonary artery conduits - Dearani, J.A.; Danielson, G.K.; Puga, F.J.; Schaff, H.V.; Warnes, C.W.; Driscoll, D.J.; Schleck, C.D.; Ilstrup, D.M.; Clarke, D.R.; Brown, J.W. (Annals of Thoracic Surgery, 2003)
Background. Pulmonary ventricle (PV) to pulmonary artery (PA) conduits have made possible the correction of many complex congenital cardiac anomalies. Methods. Between April 1964 and January 2001, 1270 patients underwent operation with conduit placement from the PV to PA. The present study evaluates late outcome of 1095 patients (612 males, 483 females) having an operation before July 1992. Mean age was 9.6 ± 8.2 years old. Diagnoses included pulmonary atresia/tetralogy of Fallot (459), transposition of the great arteries (TGA) (232), truncus arteriosus (193), double outlet right ventricle (DORV) (121), corrected TGA (49), septated univentricular heart (36), and other (5). A porcine-valved Dacron conduit was used in 730, homograft in 239, and non-valved conduit in 126. Results. Early mortality decreased from 23.5% prior to 1980 to 3.7% for the most recent decade. Mean follow-up was 10.9 years (maximum, 29 years). Actuarial survival for early survivors at 10 and 20 years was 77.0% ± 1.5% and 59.5% ± 2.6%. On univariate analysis, clinical and hemodynamic factors associated with late mortality were male gender, older age at operation, higher post-repair PV/systemic ventricle (SV) pressure ratio, higher distal PA pressure, and longer bypass time (p ≤ 0.01 for all). On multivariate analysis, independent risk factors for late mortality were male gender, older age at operation, diagnosis of TGA, corrected TGA, truncus, or univentricular heart, and PV/SV pressure ratio ≥ 0.72 (p ≤ 0.03 for all). Freedom from reoperation for conduit failure at 10 and 20 years was 55.5% ± 2.0% and 31.9% ≤ 2.7%. On multivariate analysis, independent risk factors for conduit failure were homograft conduit, diagnosis of TGA, younger age at operation, and smaller conduit size (p ≤ 0.007 for all). Reoperation for one conduit replacement was performed in 306 patients, two conduit replacements in 55 patients, three in 6 patients, and four in 3 patients. Overall early mortality for conduit replacement in this series was 4.9%; it was 1.7% for patients operated on from 1989 through 1992. At follow-up, 84% of survivors were in NYHA class I or II. Conclusions. Operations that include conduit placement and replacement can be performed with low early mortality. Younger age at operation was associated with improved late survival. The diagnosis of TGA was associated with increased risk for conduit failure, and the durability of the homograft, in this series, was inferior to the porcine-valved Dacron conduit. Quality of life was excellent for most patients despite the need for reoperation. © 2003 by The Society of Thoracic Surgeons.
Keywords: adolescent; adult; aortopulmonary septal defect; article; Blalock Taussig shunt; cardiovascular surgery; child; clinical article; congenital heart disease; Fallot tetralogy; female; follow up; great vessels transposition; heart right ventricle double outlet; human; infant; lung artery; pulmonary valve atresia; male; priority journal; survival rate; treatment outcome

Developmental outcome of patients with hypoplastic left heart syndrome treated with heart transplantation - Ikle, L.; Hale, K.; Fashaw, L.; Boucek, M.; Rosenberg, A.A. (Journal of Pediatrics, 2003)
Objective: To describe the outcome of children treated for hypoplastic left heart syndrome (HLHS) with heart transplantation. Study design: We evaluated outcomes in 26 children treated for HLHS in a single center; 13 children were evaluated with the Bayley Scales of Infant Development, Child Behavior Checklist (CBCL), and Vineland Adaptive Behavior Scales (VABS), and 13 were seen after 36 months of age and were evaluated with the Wechsler Preschool and Primary Scale of Intelligence, CBCL, and VABS at 36 to 72 months or the Wechsler Intelligence Scale for Children-III, CBCL, and VABS for those older than 72 months of age. Results: Bayley Scales of Infant Development results revealed a median Mental Developmental Index of 88 (range <50 to 102) and a Psychomotor Developmental Index of 86.5 (<50 to 113), both significantly lower than expected in the general population. Intelligence quotient results on either the Wechsler Preschool and Primary Scale of Intelligence or Wechsler Intelligence Scale for Children-III were also significantly lower than expected, with a mean verbal score of 90.5 ± 12.4, performance score of 88.9 ± 14.5, and full scale score of 88.5 ± 13.0. On the Vineland scales, 39% scored >1 SD below the mean on measures of daily living scales, 22% on the socialization subscale, 48% on the communication subscale, and 52% on the adaptive behavior scale. Conclusions: In this small population of children treated for HLHS with heart transplantation, both cognitive deficits and adaptive/behavioral abnormalities are described. Early identification with appropriate referral for services could potentially enhance the outcomes for these children.
Keywords: adaptive behavior; article; behavior disorder; clinical article; cognitive defect; controlled study; female; heart transplantation; human; hypoplastic left heart syndrome; infant; intelligence quotient; interpersonal communication; male; mental development; mental performance; outcomes research; population; priority journal; socialization; treatment outcome

Early extubation in congenital heart surgery - Neirotti, R.A.; Jones, D.; Hackbarth, R.; Fosse, G.P. (Heart Lung and Circulation, 2002)
Background: The concept of early extubation following congenital heart surgery is not new. Changes in health care have generated increasing interest in this technique. Some of the problems following surgery are related to the endotracheal tube and mechanical ventilation, and the interventions necessary to maintain them. Methods: To evaluate the impact of early extubation (within 6 h postoperatively) on children undergoing congenital heart surgery, retrospective data were obtained from records of 1000 consecutive patients. Results: Early extubation occurred in 80.2% of patients (73% in the operating room). Early extubation was not limited to simple anomalies; it was also possible for complex anomalies such as Fallot's tetralogy (including those patients with pulmonary atresia, absent pulmonary valve and complete atrioventricular septal defects; n = 106), where 91% of patients had early extubation, and Fontan operations (n = 17), where 88% did. There were no deaths related to early extubation. Preoperative intubation was a risk factor for postoperative ventilation. As expected, the patients requiring ventilation after surgery were younger, smaller and more critically ill than those that met the criteria for early extubation. Conclusions: A change in attitude combined with appropriate anaesthetic and surgical techniques permitted safe, early extubation in a large number of patients. Patient populations vary between institutions. Early extubation is not always possible, but for those patients in whom it is feasible, the benefits include simplified postoperative care and increased patient and family satisfaction. When combined with clinical practice guidelines, it can result in a significant reduction in the cost of patient care after cardiac surgery.
Keywords: anesthesiological procedure; article; breathing; congenital heart disease; critical illness; data analysis; death; extubation; Fallot tetralogy; family; Fontan procedure; health care cost; heart septum defect; heart surgery; human; infant; intubation; pulmonary valve atresia; major clinical study; medical record; patient care; patient satisfaction; physician attitude; postoperative care; postoperative period; practice guideline; preoperative period; preschool child; priority journal; pulmonary valve disease; retrospective study; risk factor; surgical technique

Arch reconstruction without circulatory arrest: Current clinical applications and results of therapy - MacDonald, M.J.; Hanley, F.L.; Reddy, V.M. (Pediatric Cardiac Surgery Annual, 2002)
Laboratory and clinical data have confirmed the deleterious effects of deep hypothermic circulatory arrest. Long-term data and rigorous neuropsychiatric data are currently sparse, but that which are available show adverse outcomes following circulatory arrest, and therefore support the use of continuous perfusion techniques. There are no available long-term data on continuous perfusion techniques with respect to neurologic outcomes, but using these techniques the incidence of postoperative seizures or other neurologic events is rare. Currently available bypass systems and microsurgical techniques have allowed continuous flow and regional perfusion to become practical alternatives. Several innovative techniques for avoiding circulatory arrest during neonatal aortic arch reconstruction for univentricular and biventricular hearts are described. It would appear prudent and desirable to provide continuous perfusion now that long-term survival after repair of even the most complex cardiac anomalies including single ventricle defects is commonplace. Copyright © 2002 by W.B. Saunders Company.
Keywords: aortic arch; aortic reconstruction; article; brain blood flow; brain perfusion; cardiopulmonary bypass; child; heart arrest; heart disease; heart single ventricle; human; infant; mental disease; microsurgery; neurologic disease; newborn; outcomes research; postoperative complication; profound induced hypothermia; regional perfusion; seizure; surgical technique; survival rate

Complications associated with heterotaxy syndrome in fontan patients - Jacobs, M.L. (Pediatric Cardiac Surgery Annual, 2002)
Enormous progress has been made in the last decade toward decreasing the risk of the Fontan operation and optimizing early and intermediate outcomes. Heterotaxy syndrome patients, with their extensive constellation of anatomic abnormalities, constitute a challenging group to manage surgically. Palliative procedures early in life are directed at creation of a satisfactory balance between pulmonary and systemic blood flow and at the same time assurance of unobstructed pulmonary venous return. For heterotaxy patients who survive beyond the newborn period, and are considered to have nonseptatable hearts, early reduction of the volume load of the functional single ventricle is extremely important. Early conversion from parallel pulmonary and systemic circulations to a superior cavopulmonary anastomosis (bidirectional Glenn or hemi-Fontan) is the preferred strategy. Traditionally, those patients with heterotaxy who survive initial surgical management have been considered a very high-risk population with respect to an eventual Fontan procedure. In heterotaxy patients it is particularly important to understand the unique and variable anatomy of the sinus node and conduction system, the potential for occult pulmonary venous obstruction, the tendency for development of atrioventricular valve regurgitation in volume loaded ventricles, and the potential for recurrent or persistent cyanosis because of intrahepatic shunting or pulmonary arteriovenous malformations. Copyright © 2002 by W.B. Saunders Company.
Keywords: article; blood volume; cyanosis; Fontan procedure; heart muscle conduction system; heart single ventricle; heterotaxy syndrome; high risk patient; human; pulmonary arteriovenous fistula; lung blood flow; lung circulation; newborn; newborn period; outcomes research; palliative therapy; pulmonary vein; pulmonary vein obstruction; risk reduction; sinus node; surgical patient; surgical risk; surgical technique; survival time; systemic circulation; venous return

Postoperative management in patients with complex congenital heart disease - Tweddell, J.S.; Hoffman, G.M. (Pediatric Cardiac Surgery Annual, 2002)
Life-threatening problems occur in the neonate and infant after cardiac surgery because of the interplay of diminished cardiac output (CO), increased metabolic demand, inflammatory responses to cardiopulmonary bypass, and maladaptive responses to stress. Therefore, the postoperative management of patients with complex congenital heart defects is directed at optimization of oxygen delivery to maintain end-organ function and promote wound healing. Traditionally, assessment of circulation in the postoperative congenital heart patient has depended on indirect assessment of CO using parameters such as blood pressure, pulses, capillary refill, and urine output. Because of the limitations of indirect and observer-dependent assessment of CO, we rely on objective measures of tissue oxygen levels for the complex postoperative patient. We have found that continuous monitoring of the mixed venous saturation (SvO2) allows for identification of acute changes in systemic oxygen delivery and frequently precedes other indicators of decreased CO. The postoperative patient can be expected to have a period of decreasing CO, and the need for intervention should be anticipated because critical low output syndrome will develop in a subset of patients. Strategies for postoperative care are developed based on the diagnosis and procedure, but optimizing SvO2 is a consistent goal. A uniform approach to airway maintenance, vascular access, and drug infusions, all universal concerns during the perioperative period, minimizes the potential for these predictable and necessary interventions to result in morbidity or mortality. Management of the postoperative single ventricle patient targets stabilization of the systemic vascular resistance through the use of vasodilators to improve systemic perfusion and simplify ventilator management. Management of any individual patient should be driven by objective analysis of available data and must include efforts to re-evaluate the treatment plan as well as to identify unanticipated problems. Copyright © 2002 by W.B. Saunders Company.
Keywords: epinephrine; amrinone; beta adrenergic receptor blocking agent; dobutamine; dopamine; glyceryl trinitrate; milrinone; nitroprusside sodium; noradrenalin; phenoxybenzamine; phentolamine; vasodilator agent; article; blood pressure; cardiopulmonary bypass; child; circulation; congenital heart disease; data analysis; drug antagonism; drug infusion; forward heart failure; heart output; heart single ventricle; heart surgery; human; inflammation; metabolism; newborn; patient care; patient monitoring; perfusion; perioperative period; postoperative care; postoperative complication; pulse rate; surgical mortality; surgical stress; surgical technique; tissue oxygenation; treatment planning; urine volume; vascular access; vascular resistance; ventilator; wound healing

Neurodevelopmental outcome after congenital heart surgery: Results from an institutional registry - Forbess, J.M.; Visconti, K.J.; Hancock-Friesen, C.; Howe, R.C.; Bellinger, D.C.; Jonas, R.A. (Circulation, 2002)
Objective - Increased survival in children with critical congenital heart disease (CHD) has raised interest in the neurodevelopmental sequelae of these lesions. This investigation is part of an institutional effort to examine the neurodevelopment of 5-year-old children following repair or palliation of CHD. Methods - We performed a battery of neuropsychological tests on a sample of 243 children between 1998 and 2001. Results - In the sample as a whole, mean full-scale (FSIQ), verbal (VIQ), and performance (PIQ) IQ scores were in the normal range (96.8±15.9, 97.8±14.6, and 96.3±17.1, 15.9, 97.8±14.6, and 96.3±17.1, respectively). Anatomic, demographic, and perioperative factors were assessed for impact on neurodevelopment. In multiple regression analysis, lower socioeconomic status (SES) and the diagnosis of velocardiofacial syndrome (VCFS) predicted a lower FSIQ (P=0.01, and P=0.001, respectively). A single ventricle diagnosis (P=0.06), longer postoperative ICU stay (P=0.08), and cumulative duration of hypothermic circulatory arrest (HCA) (P=0.09) approached significance as predictors of lower FSIQ. Conclusion - Children with CHD, on the whole, appear to be performing within the average range in terms of intellectual abilities. Lower SES and VCFS are associated with lower IQ scores. Trends toward worse outcomes were observed in single ventricle patients, biventricular patients with longer postrepair ICU stays, and patients subjected to longer periods of HCA.
Keywords: adolescent; article; child; congenital heart disease; female; heart arrest; heart surgery; human; intelligence quotient; intensive care; learning; major clinical study; male; memory; motor performance; nerve cell differentiation; neuropsychological test; outcomes research; priority journal; register; risk factor; social status; velocardiofacial syndrome; verbal behavior

Repair of hypoplastic left heart syndrome of a 4.25-kg Jehovah's witness - Forest, R.J.; Groom, R.C.; Quinn, R.; Donnelly, J.; Clark, C. (Perfusion, 2002)
The care of patients who refuse homologous transfusions has challenged cardiac surgery teams to refine blood conservation techniques and question standard transfusion practices. We cared for a newborn child with hypoplastic left heart syndrome (HLHS) whose parents refused to give consent to care for the child that involved the transfusion of homologous blood. A Norwood Stage I procedure was planned with the understanding that transfusions would be avoided, if possible. A court order was obtained that specified the conditions under which the attending physicians would transfuse the newborn. The birth weight of the patient was 4.25 kg. A low prime cardiopulmonary bypass (CPB) circuit and aggressive blood conservation techniques that included modified ultrafiltration (MUF) allowed the completion of the repair and CPB portion of the operation without the use of blood. The lowest hematocrit during CPB was 20%. After an unsuccessful attempt to separate from CPB, blood was transfused. Recovery was consistent for HLHS patients following Norwood Stage I. However, at 1 month postoperatively, the patient did require a shunt reduction for pulmonary overcirculation. Norwood Stage II repair was completed at age 4 months without donor blood. The key to a successful outcome is a well-thought-out plan by the surgeon, anesthesiologist and perfusionist. This plan should include careful monitoring of the patient's oxygenation and cardiovascular status.
Keywords: epinephrine; dopamine; milrinone; protamine sulfate; adult; article; birth weight; blood autotransfusion; cardiopulmonary bypass; case report; clinical practice; female; health care planning; hematocrit; human; hypoplastic left heart syndrome; informed consent; lung circulation; oxygenation; oxygenator; patient care; patient compliance; patient monitoring; postoperative period; priority journal; religion; standardization; surgical technique; treatment outcome; ultrafiltration; D901

Infants with single ventricle: A population-based epidemiological study - Steinberger, E.K.; Ferencz, C.; Loffredo, C.A. (Teratology, 2002)
Background: Single ventricle, a rare congenital cardiac defect, often occurs as part of a complex group of cardiovascular abnormalities. Little is known of its epidemiologic associations. Methods: Using data from the Baltimore-Washington Infant Study [BWIS], (1981-89), a population based case-control study of cardiovascular malformations, infants with single ventricle were evaluated with respect to infant and family characteristics and maternal and paternal exposures. The cases were analyzed according to presence/absence of abnormal cardio-visceral situs. Controls were 3,572 infants without heart defects randomly selected from the regional cohort of live births. Odds ratios and 95% confidence intervals were used as measures of association. Results: Single ventricle occurred in 1.25% of infants with congenital cardiovascular defects in the BWIS. Fifty-five infants had single ventricle. In 48 families (87.3%) the parents were interviewed. Thirty-three infants had normal situs and 15 had abnormal situs. Paternal alcohol consumption (OR = 2.0, 95% Cl 1.1-3.9) and paternal cigarette smoking (OR = 2.4, 95% Cl 1.1-5.1) were associated with all cases of single ventricle. These associations were even stronger in the subset of infants with abnormal situs. Maternal history of a previous induced abortion was also associated with infants born with abnormal situs (OR = 3.2, 95% Cl 1.1-11.5). Paternal marijuana use was associated with cases of single ventricle in normal situs (OR = 2.2, 95% Cl 1.0-5.2). Conclusions: Potential risk factors included paternal smoking and alcohol consumption, highlighting the need for future studies to consider environmental factors in the pathogenesis of this cardiac defect. © 2002 Wiley-Liss, Inc.
Keywords: alcohol consumption; article; cannabis addiction; cardiovascular malformation; cigarette smoking; congenital heart disease; controlled study; environmental exposure; female; heart single ventricle; human; induced abortion; major clinical study; male; newborn; pathogenesis; priority journal; risk factor

Delivery of a nonpotassium modified maintenance solution to enhance myocardial protection in stressed neonatal hearts: A new approach - Kronon, M.T.; Allen, B.S.; Halldorsson, A.; Rahman, S.; Barth, M.J.; Ilbawi, M. (Journal of Thoracic and Cardiovascular Surgery, 2002)
Objectives: This study was undertaken to compare conventional cardioplegic strategies with a new approach that uses a modified nonpotassium maintenance solution between cardioplegia doses in stressed neonatal hearts. Methods: Thirty-five neonatal piglets underwent 60 minutes of ventilator hypoxia (inspired oxygen fraction 8%-10%) followed by 20 minutes of ischemia on cardiopulmonary bypass. In 10 animals bypass was discontinued without further ischemia (stress control group). The other 25 received a warm blood cardioplegic induction and were separated into 5 groups. In 5 animals cardiopulmonary bypass was discontinued without further ischemia (cardioplegia control group); the remaining 20 underwent an additional 70 minutes of cold blood cardioplegic arrest. Five received only intermittent cardioplegia every 20 minutes, whereas 15 also received cold blood maintenance infusions between cardioplegic doses (integrated strategy). In 5 of these animals the blood was unmodified, whereas in 10 a modified nonpotassium "cardioplegia-like" solution was delivered either antegradely (n = 5) or retrogradely (n = 5). Myocardial function was assessed by pressure-volume loops (expressed as percentage of control); vascular function was assessed by coronary vascular resistance. Results: All piglets that underwent hypoxic ischemic stress alone (controls) died. Warm induction alone (cardioplegic controls) partially repaired the stress injury. Intermittent cardioplegia preserved the depressed systolic function (end-systolic elastance 40% vs 39%), increased diastolic stiffness (255% vs 239%), reduced adenosine triphosphate (10.6 vs 12.2 μg/g tissue), and elevated coronary vascular resistance at levels identical to warm induction alone; infusing unmodified blood between cardioplegia doses (standard integrated) improved results slightly. In contrast, infusion of a cold modified solution (antegrade or retrograde) between cardioplegia doses (modified integrated) completely restored systolic function (end-systolic elastance 100% and 97%, P < .001 vs intermittent and standard integrated), only minimally increased diastolic stiffness (159% and 156%, P < .001 vs intermittent and standard integrated), restored adenosine triphosphate (18.8 and 16.6 μg/g, P < .001 vs intermittent and standard integrated), and normalized coronary vascular resistance (P < .001 vs intermittent and standard integrated). This strategy was used in 72 consecutive hypoxic patients (21 arterial switch operations, retrograde; 51 Fontan procedures, antegrade) with a 2.8% mortality. Conclusions: Infusion of a cold modified solution between cardioplegic doses (modified integrated protection) significantly improved myocardial protection in the stressed neonatal heart, was effective delivered either antegradely or retrogradely, and was used successfully for hypoxic (stressed) pediatric patients.
Keywords: aspartic acid; cardioplegic agent; citric acid; glucose; glutamic acid; potassium chloride; trometamol; animal experiment; animal model; article; cardioplegia; cardiopulmonary bypass; controlled study; coronary vascular resistance; heart function; cardiac muscle; heart performance; heart protection; newborn; nonhuman; priority journal; pig

Heart transplantation in children and infants: Short-term outcome and long-term follow-up - Bauer, J.; Thul, J.; Krämer, U.; Hagel, K.J.; Akintürk, H.; Valeske, K.; Schindler, E.; Bohle, R.M.; Schranz, D. (Pediatric Transplantation, 2001)
Since 1988, 82 heart transplants have been performed in 80 infants and children. Diagnoses pretransplant were: hypoplastic left heart syndrome (HLHS) (n = 43); cardiomyopathy (n = 19); endocardial fibroelastosis (n = 6); and other complex congenital heart diseases (n = 12). Age at transplantation was < 1 yr in 61 patients. Overall survival rate was 79% at 1 yr and 73% at 5 and 10 yr. To date, 20 patients have died after transplantation. Causes of death were: rejection (eight patients); right ventricular failure (four patients); transplant coronary artery disease (TCAD) (two patients); and other causes (six patients). In the majority of patients somatic growth is not impaired, and renal function is reduced (but stable) in all patients. Two patients developed post-transplant lymphoproliferative disease, which was treated successfully. Major long-term morbidity is neurologic deficit - severe in three patients and minor in six. TCAD was present or suspected in six surviving patients. We conclude that heart transplantation in infants and children can be performed with good early and late results. Quality of life is excellent in most patients. TCAD, however, will become an increasing problem in the long term.
Keywords: azathioprine; cyclosporine; OKT 3; prednisolone; thymocyte antibody; article; cardiomyopathy; cause of death; child; congenital heart disease; controlled study; coronary artery disease; endocardial fibroelastosis; follow up; graft rejection; heart right ventricle failure; heart transplantation; human; hypoplastic left heart syndrome; immunosuppressive treatment; infant; kidney function; long term care; lymphoproliferative disease; major clinical study; morbidity; neurologic disease; quality of life; survival; treatment outcome

Medical management of chronic heart failure in children. - Ross, R.D. (American journal of cardiovascular drugs : drugs, devices, and other interventions, 2001)
Chronic heart failure (CHF) in children occurs mostly as a result of systolic dysfunction of the systemic ventricle or of congenital defects leading to large left-to-right shunts and pulmonary overcirculation. The ensuing symptoms and signs are similar in both cases, and include respiratory distress, poor feeding and growth, and hepatic congestion. Grading the severity of the symptoms accurately and reproducibly is important for studying CHF and the response to therapy. The Ross classification for young children and the New York Heart Association classification for older children are frequently utilized for such grading. The standard therapy for CHF in children consists of diuretics, to reduce cardiac preload and improve symptoms, and the maximization of nutritional support. The role of digoxin in treating CHF in children is controversial, especially regarding those children with pulmonary overcirculation where the function of the systemic ventricle is usually well preserved. As the importance of neurohormonal changes in the pathogenesis of worsening CHF is elucidated, newer medications aimed at counteracting such changes are becoming more important in the medical therapy of CHF in children. ACE inhibitors improve function and survival in adults with CHF, and they probably do the same in children with systemic ventricular dysfunction. It is less clear how effective they are in pulmonary overcirculation, but patients with high flow and low pulmonary resistance are most likely to benefit. In infants receiving treatment with ACE inhibitors, it is necessary to monitor for renal insufficiency or renal failure. beta-Adrenoceptor blockade has also been established as an effective therapy for adults with CHF with beneficial effects on survival and left ventricular function. While data for the pediatric population are limited, early studies suggest that beta-adrenoceptor antagonists (beta-blockers) may work well in infants and children with CHF. Caution must be used by starting treatment with very low dosages of beta-blockers and gradually increasing to the desired goals with close monitoring of blood pressure and heart rate. It is clear that larger multicenter trials are crucial to our ability to provide the most appropriate treatment for children with CHF. The demand for effective medical treatment will increase as more patients with palliated single ventricles survive surgery and then develop CHF from dysfunction of a hypertrophic and dilated single ventricle.
Keywords: agents interacting with transmitter, hormone or drug receptors; beta adrenergic receptor blocking agent; cardiotonic agent; digoxin; dipeptidyl carboxypeptidase inhibitor; diuretic agent; article; blood; child; clinical trial; congestive heart failure; diet therapy; human; infant; pathophysiology

Hypoplastic left-heart syndrome: The first description of the pathophysiology in 1851; translation of a publication by Dr. Bardeleben from Giessen, Germany - Gehrmann, J.; Krasemann, T.; Kehl, H.G.; Vogt, J. (Chest, 2001)
Keywords: aorta; aortic valve; article; atresia; clinical feature; death; disease course; disease severity; heart left atrium; heart left ventricle; human; hypoplastic left heart syndrome; mitral valve; newborn; patent ductus arteriosus; pathophysiology; priority journal; sucking; symptomatology

Neurodevelopmental outcomes in children after the Fontan operation - Forbess, J.M.; Visconti, K.J.; Bellinger, D.C.; Jonas, R.A. (Circulation, 2001)
Background - Previous studies of patients after the Fontan operation have reported IQ scores lower than population norms. In the past decade, changes have occurred both in surgical methods used and in the patient population undergoing Fontan palliation. The present study examined the impact of these changes on neurodevelopmental outcomes after Fontan. Methods and Results - Neuropsychological tests were administered to 27 five-year-old children after Fontan. Mean age at repair was 2 years 4 months. The present sample was compared with an earlier Fontan group (EFG) of 133 patients who underwent surgery in the 1970s and 1980s. Mean age at repair for the EFG was 7 years 3 months. Compared with EFG, the present study sample was younger at Fontan (P=0.0001) and more likely to have undergone a Norwood procedure (P=0.02), a pre-Fontan bidirectional cavopulmonary anastomosis (P<0.001), and Fontan fenestration (P=0.001). Although mean full-scale, verbal, and performance IQ scores were within 1 SD (15 points) of the population mean of 100 (93±16, 95±15, and 91±17, respectively), mean full-scale and performance IQ scores were significantly lower than this population mean (P=0.03 and P=0.01, respectively). Conclusions - Compared with a historical cohort of Fontan patients from this institution, a staged approach to Fontan earlier in life is not detrimental to neurodevelopmental outcome. Neurodevelopmental outcomes in children after Fontan are in the normal range, but performance remains lower than the general population.
Keywords: article; clinical article; controlled study; developmental disorder; follow up; Fontan procedure; human; intelligence quotient; neuropsychology; postoperative complication; preschool child; priority journal; treatment outcome

Pulmonary atresia with ventricular septal defect: Prevalence of deletion 22q11 in the different anatomic patterns - Anaclerio, S.; Marino, B.; Carotti, A.; Digilio, M.C.; Toscano, A.; Gitto, P.; Giannotti, A.; Di Donato, R.; Dallapiccola, B. (Italian Heart Journal, 2001)
Background. Pulmonary atresia with ventricular septal defect (PA-VSD) is one of the most common cardiac defects associated with DiGeorge syndrome. The pattern of the pulmonary circulation determines the complexity of this type of heart disease. The aim of this study was to establish the prevalence of DiGeorge syndrome with deletion 22q11 in patients with simple and complex PA-VSD. Methods. Since 1993 we have studied 128 consecutive patients affected by PA-VSD. In 90 of our patients the PA-VSD was considered "simple" (group I), because it was not associated with any other cardiac defects. In the other 38 children the PA-VSD was considered "complex" (group II) owing to the presence of heterotaxia, tricuspid atresia, a double-inlet left ventricle, transposition of the great arteries and congenitally corrected transposition of the great arteries. Results. In group I, 38 patients (42%) had genetic syndromes or major extracardiac anomalies; deletion 22q11 was detected in 31% of cases. Major aortopulmonary collateral arteries were present in 50% of group I patients and in 57% of those with deletion 22q11. In group II, 10 patients (26%) had genetic syndromes or major extracardiac anomalies but none had deletion 22q11 (p<0.005); in no case was the presence of major aortopulmonary collateral arteries observed (p<0.005). Conclusions. PA-VSD is an anatomically and morphogenetically heterogeneous disease: in the setting of DiGeorge syndrome or velocardiofacial syndrome, PA-VSD is associated with a peculiar cardiac pattern and is due to deletion 22, whereas in case of nonsyndromic PA-VSD or when this disease is associated with different syndromes or with other types of cardiac defects, it is due to other morphogenetic mechanisms.
Keywords: anatomy; aorta; article; child; chromosome 22q; chromosome deletion; collateral circulation; controlled study; DiGeorge syndrome; disease association; female; genetic disorder; great vessels transposition; heart disease; heart left ventricle; heart ventricle septum defect; human; infant; pulmonary valve atresia; lung circulation; major clinical study; male; morphogenesis; newborn; prevalence; pulmonary artery; tricuspid valve atresia; velocardiofacial syndrome

Long-term results of relief of subaortic stenosis in univentricular atrioventricular connection with discordant ventriculoarterial connections - Jahangiri, M.; Shinebourne, E.A.; Ross, D.B.; Anderson, R.H.; Lincoln, C. (Annals of Thoracic Surgery, 2001)
Background. We set out to examine the long-term results of relief of subaortic stenosis by enlargement of ventricular septal defect in patients with univentricular atrioventricular connection to a dominant left ventricle and discordant ventriculoarterial connections. Methods. Twenty-four patients underwent enlargement of ventricular septal defect between 1985 and 1998 at a median age of 3.2 years (range, 3 weeks to 14 years). Ten patients were younger than 1 year of age. Eighteen had undergone previous banding of the pulmonary trunk, 9 of whom also required repair of coarctation of the aorta. The median subaortic gradient before enlargement was 46 mm Hg. Twenty-three patients had a patch to enlarge the rudimentary right ventricle. Results. Five patients (21%) died in the early postoperative period. The overall survival at 1 and 3 years was 73%, and at 5 and 10 years was 68% and 60%, respectively. Complete heart block requiring insertion of a pacemaker occurred in 2 patients (8%). A Fontan operation was performed in 10 patients, 5 underwent a bidirectional Glenn procedure, and 2 required Cardiac transplantation. Follow-up was complete in all survivors at a median time of 6.7 years (range, 8 months to 13 years). From the earlier part of the series, 3 patients experienced aortic insufficiency and 2 had recurrent obstruction. Factors adversely affecting survival were age younger than 1 year at operation and presence of obstruction within the aortic arch. Conclusions. Our experience shows that, in patients with univentricular atrioventricular connection to a dominant left ventricle and subaortic stenosis, enlargement of the ventricular septal defect provides satisfactory relief of obstruction except in those younger than 1 year of age, and those who have associated obstruction in the aortic arch. © 2001 by The Society of Thoracic Surgeons.
Keywords: aortic arch; subvalvular aortic stenosis; article; atrioventricular dissociation; child; clinical article; Fontan procedure; heart block; heart ventricle septum defect; human; cardiac rhythm management device; patient satisfaction; postoperative period; priority journal; survival; treatment outcome

Hypoplastic left heart syndrome: factors influencing therapeutic choice. - Corrow, C.; Lapuk, S.; Mazzarella, K.; Sable, A.; Leopold, H.; Eisenfeld, L. (Connecticut medicine, 2001)
Parent's choices among therapeutic options for their infants born with hypoplastic left heart syndrome are difficult and controversial. Currently, management options include surgical reconstruction, cardiac transplantation, and comfort measures only. We retrospectively reviewed medical records of 47 patients (1989-1999) to create a database of clinical features of infants who received either an operation or comfort care only. Eleven families were interviewed by means of a structured questionnaire pertaining to their experience and reasons for their choice. Of the 47, 20 were prenatally diagnosed and nine of these (45%) aborted. The remaining 38 of the 47 were liveborns. Of the 38, 20/38 (53%) chose comfort care only. The other 18 chose operation. Although 17 were able to survive until first stage repair, only 8/17 (47%) survived beyond five months. At the time of last contact (ages one to 4.5 years), 5/17 (29%) remained alive. Over the nine years an increasing proportion of parents chose operative reconstruction; 8/11 (73%) for 1996-99 vs 10/27 (37%) for 1989-1995. Interviewed families who chose comfort care were more likely to believe the rate of survival following operation was poor, quality of life was diminished, and seemed concerned that their infant would suffer. Influence by optimistic physicians at surgical centers seemed important for an operative choice. Most suggested that provision of written materials, professional family counseling, and support groups of hypoplastic left heart syndrome families are or would be helpful.
Keywords: adult; article; decision making; female; human; hypoplastic left heart syndrome; induced abortion; infant; male; newborn; palliative therapy; parent; pregnancy; psychological aspect; questionnaire; retrospective study

What syndrome is this? - Al-Khenaizan, S.; Al-Sannaa, N.; Teebi, A.S. (Pediatric Dermatology, 2001)
Keywords: article; case report; child; ectodermal dysplasia; Ellis van Creveld syndrome; female; human; hypoplastic left heart syndrome; patent ductus arteriosus; polydactyly; priority journal

The Fontan procedure for tricuspid atresia: Early and late results of a 25-year experience with 216 patients - Mair, D.D.; Puga, F.J.; Danielson, G.K. (Journal of the American College of Cardiology, 2001)
OBJECTIVES: We assessed the operative and late mortality and the present clinical status of 216 patients with tricuspid atresia who had a nonfenestrated Fontan procedure performed at the Mayo Clinic in the 25-year period 1973 to 1998. BACKGROUND: The Fontan operation eliminates the systemic hypoxemia and ventricular volume overload characteristic of prior forms of palliation. However, it originally did so at the cost of systemic venous and right atrial hypertension, and the long-term effects of this "price" were unknown when the procedure was initially proposed. METHODS: We reviewed the clinical records of the 216 patients retrospectively. These were arbitrarily grouped into early (1973 through 1980), middle (1981 through 1987) and late (1988 through 1997) surgical eras. Patient outcome was also analyzed according to age at surgery. Operative and late mortality rates were determined and present clinical status was ascertained in 167 of 171 surviving patients. RESULTS: Overall survival was 79%. Operative mortality steadily declined and was 2% (one of 58 patients) during the most recent decade. Late survival also continues to improve. Age at operation had no effect on operative mortality, and late mortality was significantly increased only in patients who were operated on at age 18 years or older. Eighty-nine percent of surviving patients are currently in New York Heart Association class I or II. CONCLUSIONS: The initial 25-year experience with the nonfenestrated Fontan procedure for tricuspid atresia has been gratifying, with most survivors now leading lives of good quality into adulthood. These results justify continued application of this procedure for children born with tricuspid atresia. © 2001 by the American College of Cardiology.
Keywords: adult; article; child; follow up; Fontan procedure; health status; heart ventricle overload; human; hypertension; hypoxemia; major clinical study; palliative therapy; priority journal; quality of life; surgical mortality; survival rate; treatment outcome; tricuspid valve atresia

Atrial and ventricular electromechanical function in 1-ventricle hearts: influence of atrial flutter and Fontan procedure. - Li, W.; Sarubbi, B.; Sutton, R.; Somerville, J.; Gibson, D.; Henein, M.Y. (Journal of the American Society of Echocardiography : official publication of the American Society of Echocardiography, 2001)
OBJECTIVE: Echocardiography was used to study electromechanical atrial and ventricular function in adult patients with a 1-ventricle heart who were in sinus rhythm to better understand the recurrence of atrial flutter in these conditions. Patients who had recent atrial flutter, with and without the Fontan procedure, were compared with those who had no arrhythmia. METHODS: This was a prospective study that used M-mode and 2-dimensional Doppler echocardiography and electrocardiography. Conventional measurements were used to evaluate ventricular long-axis function. Basic data were drawn from case notes. The setting was a designated quaternary service for grown-up congenital heart patients (GUCH) in a tertiary referral center for cardiology and cardiac surgery. From January 1997 to February 1998, 26 consecutive adult patients (aged >16 years) with a heart with one functioning ventricle and a history of atrial flutter were studied: group 1, with non-Fontan palliative surgery or no surgery (10 patients), and group 2, with Fontan-type repair (16 patients). Also studied were 20 patients with a 1-ventricle heart but no history of atrial flutter. These 20 patients were divided into 2 groups: control 1, which comprised 14 patients with previous shunts or no surgery, and control 2, which consisted of 6 patients with Fontan repair. RESULTS: P-wave duration on the electrocardiogram was similar in the 4 patient groups, but the amplitude was reduced in group 2 and control 2 (patients with Fontan surgery) (P <.016). Bifid P wave was seen in 5 (50%) of 10 patients in group 1 and in 6 (43%) of 14 patients in control 1, but it was not seen in patients with Fontan (P <.01). Ventricular systolic and diastolic dimensions and fractional shortening were not different between patients and controls. Right atrial transverse dimensions were greater in group 2 patients compared with those in controls. Significant atrioventricular valve regurgitation was seen in 9 of 10 group 1 patients but in none of the others. Right-sided total long-axis excursion and atrial A-wave amplitude were depressed in group 2 patients compared with the values in the others. The onset of right atrial shortening was delayed by 50 ms in group 2 compared with control 2, whereas the left atrial shortening was delayed by 30 ms in group 1 compared with control 1. This particular disturbance remained 6 months after cardioversion. CONCLUSION: In 1-ventricle hearts, significant atrioventricular valve regurgitation is commonly associated with atrial flutter in patients who did not undergo the Fontan procedure, and with electromechanical disturbances in those who did. Recognition of disturbances in ventricular long-axis function may thus assist in the identification of patients with a 1-ventricle heart who are prone to atrial flutter.
Keywords: adolescent; adult; article; chi square distribution; congenital malformation; Doppler echocardiography; echography; electrocardiography; female; Fontan procedure; heart atrium flutter; heart muscle conduction system; heart ventricle; human; male; methodology; middle aged; palliative therapy; pathophysiology; prospective study

Quality of life and perceived health status in surviving adults with univentricular heart - Saliba, Z.; Butera, G.; Bonnet, D.; Bonhoeffer, P.; Villain, E.; Kachaner, J.; Sidi, D.; Iserin, L. (Heart, 2001)
Objective - To evaluate the quality of life in patients with univentricular heart and to determine the impact of sociodemographic and clinical characteristics. Design and setting - Retrospective, cross sectional study conducted in a regional paediatric cardiology centre. Patients - The health records of 89 survivors with univentricular heart (median age 21 years; range 17-49 years) were reviewed. Sixty seven answered the Duke questionnaire. Sociodemographic and clinical variables were similar in the responders and non-responders. The impact of sociodemographic and clinical variables on individual Duke's measures was assessed. Results - The Duke scores of adults with univentricular heart were similar to the normal population. Cyanosis predicted a worse score for physical (p = 0.05) and perceived health measures (p = 0.02). A higher educational level predicted a better score for physical (p = 0.004), mental (p = 0.01), and general health measures (p = 0.02). Orthopaedic problems worsened the social score (p = 0.05). Psychosocial problems worsened the pain score (p = 0.04). In comparison with the other anatomical types, mitral atresia worsened the perceived health score (p = 0.02). Patients younger than 23 years scored better for almost all health and dysfunction measures. Conclusions - Despite repeated interventions and other disease related everyday stresses, a selected group of adults with univentricular heart had a satisfying quality of life.
Keywords: adolescent; adult; age; article; clinical feature; controlled study; cyanosis; demography; health status; heart disease; heart single ventricle; human; major clinical study; mental health; mitral valve atresia; orthopedics; prediction; priority journal; psychosocial disorder; quality of life; retrospective study; scoring system; social aspect; physiological stress

Neurodevelopmental outcome of patients after the Fontan operation: A comparison between children with hypoplastic left heart syndrome and other functional single ventricle lesions - Goldberg, C.S.; Schwartz, E.M.; Brunberg, J.A.; Mosca, R.S.; Bove, E.L.; Schork, M.A.; Stetz, S.P.; Cheatham, J.P.; Kulik, T.J. (Journal of Pediatrics, 2000)
Objective: To compare neurodevelopmental outcome (NDO) in patients with hypoplastic left heart syndrome (HLHS), other functional single ventricle lesions, and the standard population and to investigate predictors of NDO in the population of children with functional single ventricle (FSV). Study design: A time- and age-defined cohort of patients with the Fontan circulation was recruited to participate in neurodevelopmental testing, behavioral evaluation, and imaging of the central nervous system. The Wechsler Intelligence test was the primary measure of NDO. Analysis included comparison of patients with HLHS with other patients with functional single ventricles. Other potential clinical predictors of NDO were investigated. Results: The mean Full Scale Wechsler Intelligence score was 101.4 ± 5.4. For the HLHS subgroup the mean Full Scale Wechsler score was 93.8 ± 7.3, and for the non-HLHS subgroup it was 107.0 ± 7.0. Although the HLHS group had significantly lower scores than the non-HLHS subgroup, neither subgroup scored significantly different from the standard population on the Wechsler Scales. Socioeconomic status, circulatory arrest, and perioperative seizures also were predictive of neurodevelopmental outcome. Conclusion: Neurodevelopmental and behavioral outcome in patients who have undergone the Fontan procedure including patients with HLHS is good in the preschool and early school years, with Wechsler Intelligence scores generally in the normal range.
Keywords: article; brain development; child; child behavior; Fontan procedure; heart arrest; heart single ventricle; human; hypoplastic left heart syndrome; intelligence test; major clinical study; prediction; priority journal; seizure; socioeconomics

Postoperative nitric oxide therapy in children with congenital heart disease. Can the need be predicted? - Laitinen, P.O.; Räsänen, J.; Sairanen, H. (Scandinavian Cardiovascular Journal, 2000)
The necessity for postoperative inhaled nitric oxide (NO) therapy and predictive factors for that need were retrospectively analysed in 457 paediatric patients at risk of pulmonary hypertensive events following open-heart surgery for congenital heart disease. Inhaled NO was given postoperatively to 46% of the study group and to 23% of all patients undergoing open-heart surgery during the study period. Factors associated with increased need for postoperative NO were age <1 year, Down's syndrome, preoperative pulmonary hypertension and increased pulmonary vascular resistance. Using a multivariate model based on these factors, 73% of the patients who were given NO were identified. Thus, in a setting with unrestricted access to NO therapy, almost half of the patients with cardiac lesions that commonly give rise to postoperative pulmonary hypertension were given postoperative NO. Seventy-three percent of postoperative NO treatment was associated with a relatively small number of pre- and perioperative patient-related risk factors.
Keywords: nitric oxide; age; aortopulmonary septal defect; arterial trunk; article; cardiomyopathy; cardiopulmonary bypass; child; congenital heart disease; controlled study; Down syndrome; female; great vessels transposition; heart atrium septum defect; heart single ventricle; heart ventricle septum defect; human; infant; lung vascular resistance; major clinical study; male; multivariate analysis; open heart surgery; postoperative care; prediction; preoperative evaluation; priority journal; pulmonary hypertension; retrospective study; risk factor

Surgical treatment of coarctation complex in neonates and infants. - Yamauchi, H.; Fujii, M.; Iwaki, H.; Ishii, Y.; Saji, Y.; Maruyama, Y.; Yamashita, H.; Uchikoba, Y.; Fukazawa, R.; Okubo, T.; Ogawa, S.; Tanaka, S. (Journal of Nippon Medical School = Nihon Ika Daigaku zasshi, 2000)
BACKGROUND: There remains controversy regarding the appropriate surgical treatment of coarctation of the aorta associated with intracardiac anomalies in neonates and infants. Furthermore, the relative benefits of one versus two-stage repair, and subclavian flap aortoplasty versus end-to-end anastomosis for some of these lesions, remain controversial. The purpose of this paper is to review our experience with two-stage repair using subclavian flap aortoplasty and to seek an appropriate procedure. METHODS AND RESULT: From June 1996 to November 1999, thirteen patients underwent subclavian flap aortoplasty in our department. The age range was 16 to 101 days (mean 52 days), and the body weight range was 1.9 to 4.5 kg (mean 3.0 kg). Anatomic diagnosis was coarctation with ventricular septal defect (six patients), double outlet right ventricle (two patients), atrioventricular canal defect (one patient), tricuspid atresia (two patients), mitral atresia (one patient), and single atrium and subaortic stenosis (one patient). There was one hospital death in our series due to the progression of pulmonary hypertension 3 months after the operation. The mean follow up for remaining twelve patients was 28 months (range 7 approximately 48 months). There was one reoperation for recurrent coarctation. Three patients underwent pulmonary artery plasty in a second operation because of right pulmonary artery stenosis. We performed the definitive operation for six patients with coarctation with ventricular septal defect and two patients with double outlet right ventricle, and we performed a bidirectional cavopulmonary shunt for four univentricular hearts who are candidates for the Fontan operation. Two patients required Damus-Kaye-Stansel procedure to release restrictive bulboventricular foramen. Three patients underwent a modified Fontan operation after these palliations. In our series, the intraoperative mortality rate for subclavian flap aortoplasty was 0% and the post operative mortality rate was 7.7% (1/13). Ten patients underwent the final operation successfully, and further two patients are considered good candidates for the final operation. The overall mortality was 7.7% (1/13). CONCLUSION: Two-stage repair appears to offer a good prognosis for neonates and infants with a coarctation complex. Subclavian flap aortoplasty showed the lowest rate of restenosis. However, late mortality may be associated with the progression of pulmonary vascular disease and the presence of associated severe cardiac anomalies. Although Fontan candidates need staged operations, if biventricular repair is feasible, one-stage repair would be a reasonable procedure considering the progression of the pulmonary vascular disease and the distortion of the pulmonary artery due to pulmonary artery banding. It would appear to improve the quality of life of those children if a one-stage operation can be performed with reasonable risk and good midterm outcome.
Keywords: aorta; aortic coarctation; article; cardiovascular surgery; congenital heart malformation; female; follow up; human; infant; male; methodology; newborn; plastic surgery; retrospective study; treatment outcome

Ethical issues in parental decision-making. An interview study of mothers of children with hypoplastic left heart syndrome - Vandvik, I.H.; Forde, R. (Acta Paediatrica, International Journal of Paediatrics, 2000)
It is unclear how parents make life-and-death decisions on behalf of their children. To address this issue we interviewed 20 mothers whose children were born with hypoplastic left heart syndrome (HLHS), 10 whose child survived the operations and 10 mothers who chose comfort care. Semistructured interviews lasting from 1.5 to 3.5 h took place on median 4.6 (range 2 .5-6) years after birth. The mothers who chose comfort care had more years of education (p = 0.03), reported a better childhood environment (p= 0.05) and had more often been employed in the healthcare services. The two groups described the information received in similar terms. The main motive for choosing surgery was that this was perceived to be the only acceptable choice. The motive for choosing non-treatment was to prevent the child from suffering. Lack of knowledge about long-term outcome, a state of shock and short time to deliberate limit the parents' possibilities for making autonomous choices. Autonomous decisions may be neither possible nor desirable for all parents. The care perspective, which highlights the parents' preferences, resources and values, should represent ethical guidelines for care providers willing to decide on behalf of the child.
Keywords: article; child care; child parent relation; clinical article; controlled study; decision making; education; environment; ethics; female; health service; heart surgery; human; hypoplastic left heart syndrome; informed consent; maternal care; priority journal; survival

Parental preferences for primary and specialty care collaboration in the management of teenagers with congenital heart disease - Miller, M.R.; Forrest, C.B.; Kan, J.S. (Pediatrics, 2000)
Objectives. We examined parental preferences for locus of service delivery for their teenager's congenital heart disease (CHD) and the influence of disease severity, sociodemographic factors, and insurance on these preferences. Methods. A consecutive sample of parents of teenagers followed in a pediatric cardiology clinic completed a mailed questionnaire. Disease severity was classified as low (≤1 cardiovascular procedure), moderate (>1 cardiovascular procedure), and high (cyanosis or single ventricle physiology). Results. Eighty-six of 148 parents responded (58%): 40, low severity; 36, moderate severity; and 10, high severity of illness. Parents preferred using primary care providers (PCPs) as a point of first contact for all 11 of 11 general health concerns and 5 of 7 potential cardiovascular-related concerns: chest pain (52%), syncope (73%), seeming seriously ill (79%), sports physical examination (79%), and endocarditis prophylactic antibiotics (94%). Increasing disease severity was significantly associated with preferring cardiologists for 6 of 7 cardiovascular-related concerns. Overall, 58% of parents viewed their care as a PCP- cardiologist comanagement model versus a cardiologist-dominated model. Lower family income (odds ratio [OR]: 1.5; confidence interval [CI]: 1.0-2.2) and severity of illness (OR: 2.1; CI: 1.0-4.4.) were associated with a comanagement model of health care versus a cardiologist-dominated model. Conclusions. This study suggests that the majority of parents of teenagers with CHD prefer to use their teenager's PCP for all routine health care needs and many cardiovascular health needs. Severity of illness and family income are positively associated with greater preference for cardiologist care.
Keywords: adolescent; article; cardiovascular disease; chronic disease; congenital heart disease; disease severity; health insurance; human; major clinical study; medical specialist; parental behavior; patient care; primary health care; priority journal

Hypoplastic left heart syndrome: Valuing the survival - Williams, D.L.; Gelijns, A.C.; Moskowitz, A.J.; Weinberg, A.D.; Ng, J.H.; Crawford, E.; Hayes, C.J.; Quaegebeur, J.M. (Journal of Thoracic and Cardiovascular Surgery, 2000)
Objective: To examine the survival, developmental status, quality of life, and direct medical costs of children with hypoplastic left heart syndrome who have undergone stage I, II, and III reconstructive surgery. Methods: A total of 106 children underwent staged repair for classic hypoplastic left heart syndrome between February 1990 and March 1999 (stage I: 106; stage II: 49; stage III: 25; 4 converted to heart transplantation). Survival was analyzed by the Kaplan-Meier method. In a cross-sectional study, parents assessed quality of life by completing the Infant/Toddler Child Health Questionnaire or Child Health Questionnaire Parent Format-28; they assessed developmental progress by completing the Ages and Stages Questionnaire. The ratio-of-costs-to-charges method was used to derive hospital costs, and payments were used to capture physician time and wholesale pricing for outpatient medications. Results: Institutional 1-year and 5-year actuarial survivals were 58% and 54%. Birth weight, the need for preoperative inotropic drugs, and surgical experience were predictors of survival. Norwood I patients achieved fewer developmental benchmarks than those who survived to subsequent stages. Child Health Questionnaire Parent Format-28 mean summary scores for physical and psychosocial health were 48.5 ± 6.3 and 42.8 ± 9.9. The median inpatient costs for stage I, II, and III repairs were $51,000, $33,892, and $52,183, respectively. Monthly outpatient and readmission costs were less than 10% of total costs. Conclusion: A prospective, large-scale study of the comprehensive outcomes of staged repair and transplantation is needed. This study will need to address the longer- term developmental and quality-of-life outcomes, as well as the long-term cost effectiveness of these procedures.
Keywords: inotropic agent; article; child; child health; child hospitalization; health care cost; heart surgery; heart transplantation; hospital cost; human; hypoplastic left heart syndrome; infant; major clinical study; newborn; outpatient care; priority journal; quality of life; survival

Cardiac abnormalities in birth asphyxia. - Ranjit, M.S. (Indian journal of pediatrics, 2000)
Cardiac abnormalities in birth asphyxia were first recognised in the 1970s. These include (i) transient tricuspid regurgitation which is the commonest cause of a systolic murmur in a newborn and tends to disappear without any treatment unless it is associated with transient myocardial ischemia or primary pulmonary hypertension of the newborn (ii) transient mitral regurgitation which is much less common and is often a part of transient myocardial ischemia, at times with reduced left ventricular function and, therefore, requires treatment in the form of inotropic and ventilatory support (iii) transient myocardial ischemia (TMI) of the newborn. This should be suspected in any baby with asphyxia, respiratory distress and poor pulses, especially if a murmur is audible. It is of five types (A to E) according to Rowe's classification. Type B is the most severe with respiratory distress, congestive heart failure and shock. Echocardiography helps to rule out critical left ventricular obstructive lesions like hypoplastic left heart syndrome or critical aortic stenosis. ECG is very important for diagnosis of TMI, and may show changes ranging from T wave inversion in one lead to a classical segmental infarction pattern with abnormal q waves. CPK-MB may rise and echocardiogram shows impaired left ventricular function, mitral and/or tricuspid regurgitation, and at times, wall motion abnormalities of left ventricle. Ejection fraction is often depressed and is a useful marker of severity and prognosis. Treatment includes fluid restriction, inotropic support, diuretics and ventilatory resistance if required (v) persistent pulmonary hypertension of the newborn (PPHN). Persistent hypoxia sometimes results in persistence of constricted fetal pulmonary vascular bed causing pulmonary arterial hypertension with consequent right to left shunt across patent ductus arteriosus and foramen ovale. This causes respiratory tension and right ventricular failure with systolic murmur of tricuspid, and at times, mitral regurgitation. Treatment consists of oxygen and general care for mild cases, ventilatory support, ECMO and nitric oxide for severe cases. Cardiac abnormalities in asphyxiated neonates are often underdiagnosed and require a high index of suspicion. ECG and Echo help in early recognition and hence better management of these cases.
Keywords: article; heart disease; heart muscle ischemia; human; mitral valve regurgitation; newborn; newborn hypoxia; persistent pulmonary hypertension; time; tricuspid valve regurgitation

Extracardiac conduit Fontan procedure: Early and intermediate results - Haas, G.S.; Hess, H.; Black, M.; Onnasch, J.; Mohr, F.W.; Van Son, J.A.M. (European Journal of Cardio-thoracic Surgery, 2000)
Objective: The extracardiac Fontan procedure, as compared with classic atriopulmonary connections, may have the potential for optimizing ventricular and pulmonary vascular function by maximizing the laminar flow principle, by the avoidance of intra-atrial suture lines and cardiac manipulation, and by minimizing cardiopulmonary bypass time. In this study the clinical results of this procedure are assessed. Methods: From January 1990 until January 1997, 45 patients (33 males and 12 females) with a median age of 4.0 years (range 2.7-38 years) underwent an extracardiac Fontan procedure for univentricular physiology. The underlying diagnoses included tricuspid atresia (n=19), double-inlet left ventricle (n=11), and complex anomalies (n=15). Forty patients (89%) were in sinus rhythm. The median ventricular ejection fraction was 60%. In 37 patients (82%) the procedure was staged. Results: Median cardiopulmonary bypass time was 72 min, with a decrease to a median time of 24 min in the last ten patients. Aortic cross-clamping was avoided in 33 patients (73%). The intraoperative Fontan pressure and transpulmonary gradient were low: 13.6±3.2 and 8.5±3.9 mmHg, respectively. Transient supraventricular tachyarrhythmias were observed in six patients (13%). There was no early or late mortality. At a median follow-up of 64 months (range 26-105 months), 39 patients (87%) were in NYHA class I, four (9%) were in NYHA class II, and two (4%) were in class III. Forty patients (89%) remained in sinus rhythm. The median ventricular ejection fraction was 59%. The median arterial oxygen saturation raised from 82% preoperatively to 97%. Functional class (P=0.02), maintenance of sinus rhythm (P=0.04), and preservation of ventricular function (P=0.05) was superior in patients who were appropriately staged. None of the patients had atrial thrombus, chronic pleural effusions, or protein losing enteropathy. Conclusions: In the majority of patients, the extracardiac Fontan procedure, when performed as a staged procedure, provides excellent early and midterm results in terms of quality of life, maintenance of sinus rhythm, and preservation of ventricular function. Copyright (C) 2000 Elsevier Science B.V.
Keywords: adolescent; adult; anastomosis; article; cannulation; cardiopulmonary bypass; child; clinical article; clinical trial; comparative study; controlled clinical trial; controlled study; female; Fontan procedure; heart single ventricle; heart ventricle ejection; Holter monitoring; human; male; priority journal; supraventricular tachycardia

Evolution of the Fontan procedure in a single center - Bando, K.; Turrentine, M.W.; Park, H.J.; Sharp, T.G.; Scavo, V.; Brown, J.W. (Annals of Thoracic Surgery, 2000)
Background. Surgical approaches to single ventricle variants include staged, fenestrated, and completed Fontan operations. This study compares outcomes with these modifications of the Fontan operation at a single center. Methods. Preoperative risk factors and operative results were analyzed by multivariate techniques in 129 patients undergoing modified Fontan operations since March 1988. Results. Overall early and late mortality was 5.41% and 0.8%, respectively. Before 1993, completed Fontan operation using right atrial to pulmonary artery anastomoSis without fenestration was performed in the majority of patients (44 of 58; 76%). During this period, 10 of 17 patients at high risk had completed Fontan with three takedowns. In 1994, the staged hemi-Fontan and modified Fontan with a lateral tunnel anastomosis and with or without small fenestration (2.5 to 4 mm) were introduced. The majority of patients at high risk during this period underwent hemi-Fontan followed by fenestrated Fontan with no takedowns. Late atrial dysrhythmias occurred in 6 patients (4.7%), generally with larger fenestrations or right atrial to pulmonary anastomose. Three patients (2.3%) had a stroke, 2 with large (≥ 4 mm) fenestrations. Of 38 fenestrations, 32 (84%) closed spontaneously by 1 year. No protein-losing enteropathy occurred. Most patients (118 of 121) were in New York Heart Association class I/II 4.5 years postoperatively. By multivariate analysis, only Down's syndrome (p < 0.001) predicted early mortality, whereas both Down's syndrome and a systemic right ventricle decreased late survival (p < 0.006). Conclusions. Proper selection of patients modifications of the Fontan procedure resulted in excellent early and late survival with a low incidence of atrial dysrhythmia and stroke. Midterm functional outcomes were excellent. (C) 2000 by The Society of Thoracic Surgeons.
Keywords: adolescent; adult; article; child; cyanotic heart disease; Down syndrome; Fontan procedure; heart atrium arrhythmia; heart single ventricle; human; infant; major clinical study; patient selection; preoperative evaluation; priority journal; risk factor; sternotomy; cerebrovascular accident; surgical approach; surgical technique; survival rate; thromboembolism

Neurodevelopmental outcome and lifestyle assessment in school-aged and adolescent children with hypoplastic left heart syndrome - Mahle, W.T.; Clancy, R.R.; Moss, E.M.; Gerdes, M.; Jobes, D.R.; Wernovsky, G. (Pediatrics, 2000)
Objectives. The purposes of this study are to describe the quality of life and cognitive function in school-aged children who have undergone staged palliation for hypoplastic left heart syndrome (HLHS), and to identify factors that are predictive of neurodevelopmental outcome in this population. Methods. School-aged survivors with HLHS who had undergone palliative surgery at our institution were identified and mailed a questionnaire to assess subjectively quality of life, school performance, and incidence of medical complications. A subgroup of local patients underwent standardized testing of cognitive function and neurologic examination. These patients were compared with the larger (remote) group of questionnaire respondents to determine whether results may be generalizable to the entire HLHS population. Potential predictors of neurologic and cognitive outcome were tested for their association with test scores using multivariate regression analysis. Results. Questionnaire results were obtained from 115 of 138 eligible children (83%; mean age: 9.0 ± 2.0 years). Standardized testing was performed in 28 of 34 (82%) eligible local patients (mean age: 8.6 ± 2.1 years). The majority of parents or guardians described their child's health as good (34%) or excellent (45%) and their academic performance as average (42%) or above average (42%). One third of the children, however, were receiving some form of special education. Chronic medication usage was common (64%); the incidence of medical complications was comparable to that previously reported in children with Fontan physiology. Cognitive testing of the local group demonstrated a median full scale IQ of 86 (range: 50-116). Mental retardation (IQ: <70) was noted in 18% of patients. In multivariate analysis, only the occurrence of preoperative seizures predicted lower full scale IQ. Conclusions. Although the majority of school-aged children with HLHS had IQ scores within the normal range, mean performance for this historical cohort of survivors was lower than that in the general population.
Keywords: academic achievement; adolescent; article; attention deficit disorder; behavior disorder; cognitive defect; cognitive development; female; health status; human; hypoplastic left heart syndrome; intelligence quotient; language development; lifestyle; major clinical study; male; neurologic disease; priority journal; quality of life; school child; seizure

Electrocardiographic ST-segment depression in children with Fontan circulation - Rydberg, A. (Clinical Physiology, 2000)
Despite successful operation, many patients palliated with a Fontan-type procedure continue to show effort limitation. We previously observed that these children showed electrocardiographic ST depression during exercise tests. The purpose of the study was to investigate whether electrocardiographic ST depression is a common finding in children with Fontan circulation. Forty-two children in two groups were examined: group A consisted of 14 patients who had all undergone a modified Fontan procedure, and group B consisted of 28 children with a structurally normal heart, matched for length, weight and gender to group A. Complete echocardiographic examinations were performed in all patients and controls. All 14 patients and all 28 healthy children underwent standard 24 h ambulatory electrocardiographic monitoring. All the recordings were analysed by a PC-based Holter system where an analysis of ST changes was performed. Seven patients and 14 matched healthy children were exercised on bicycle ergometers. Four patients and eight matched healthy children underwent exercise testing by walking/running a treadmill. Ten of 13 patients analysed had significant ST depressions on ambulatory electrocardiogram (> 0.20 mV). Three of the 10 patients with ST depression were on digoxin. Three patients showed depressions of the ST segment in the electrocardiogram during exercise, with a maximal depression of 0.20-0.35 mV. None of the 28 matched healthy children showed electrocardiographic ST depression on the ambulatory 24 h ECG. These findings indicate that ST depression in daily activity is a common finding in children with Fontan circulation.
Keywords: digoxin; adolescent; ambulatory monitoring; article; bicycle; child; clinical article; congenital heart malformation; controlled study; electrocardiogram; ergometer; exercise test; female; Fontan procedure; Holter monitoring; human; male; normal human; priority journal; ST segment; ST segment depression; treadmill

Outcome of patients with cyanotic congenital heart disease undergoing a second systemic-to-pulmonary artery shunt - Aeba, R.; Katogi, T.; Takeuchi, S.; Kawada, S. (Journal of Cardiovascular Surgery, 2000)
Background. Multiple systemic-to-pulmonary artery shunts often represent a deviation from the initial management strategy for cyanotic congenital heart disease. This study analysed the outcome in patients undergoing a second shunt. Methods. Between 1965 and 1998, 80 patients required a second shunt. Patient age ranged from 11 days to 11.2 years at the initial shunt, and 4 months to 25.6 years at the second shunt. The interval between shunts ranged from 11 days to 19.6 years. Results. The patient survival rates at 1, 6, 12, 60 and 120 months following the second shunt were 95.0 ± 2.4%, 92.5 ± 3.0%, 87.4 ± 3.7%. 82.4 ± 4.5% and 74.8 ± 5.8%, respectively. Although excess pulmonary flow was not encountered after the second shunt, mode and incidence of morbidity were otherwise similar to the first one. Between 9 months and 7.5 years after the second shunt, 24 patients underwent successful definitive repair. Multivariable analysis identified pulmonary atresia (p = 0.027) and a short (< 1 year) interval between the two shunts (p = 0.034) as the independent risk factors for long-term shunt failure. Single ventricle physiology (p = 0.002) and a central approach for the second shunt (p = 0.016) were independent risk factors for lack of application, or failure of intracardiac definitive repair. Conclusions. A significant limitation in longevity and quality of life is common in patients requiring a second shunt, especially those associated with pulmonary atresia, the single ventricle physiology heart, or ungraftably hypoplastic contralateral branch pulmonary artery to the first shunt. Since excess pulmonary blood flow leading to congenital heart failure and/or ventricular diastolic dysfunction is unlikely, all patients who preclude definitive repair due to decreased pulmonary blood flow even after the first shunt should be shunted again.
Keywords: adolescent; adult; artery blood flow; article; child; cyanotic heart disease; human; infant; pulmonary valve atresia; major clinical study; multivariate analysis; newborn; pulmonary artery; reoperation; shunting; survival rate

Impact of early ventricular unloading on exercise performance in preadolescents with single ventricle Fontan physiology - Mahle, W.T.; Wernovsky, G.; Bridges, N.D.; Linton, A.B.; Paridon, S.M. (Journal of the American College of Cardiology, 1999)
OBJECTIVES: We sought to determine if early ventricular volume unloading improves aerobic capacity in patients with single ventricle Fontan physiology. BACKGROUND: Surgical strategies for patients with-single ventricle include intermediate staging or early Fontan completion to reduce the adverse affects of prolonged ventricular volume load. The impact of this strategy on exercise performance has not been evaluated. METHODS: Retrospectively, we reviewed the exercise stress test results of all preadolescents with single unloading was ventricle Fontan physiology. 'Volume unloading' was considered to have occurred at the time of bidirectional cavopulmonary anastomosis or at the time of Fontan surgery in those patients who did not undergo intermediate staging. Potential predictors of aerobic capacity were analyzed using multivariate regression. RESULTS: The patients (n = 46) achieved a mean percentage predicted of maximal oxygen consumption (V̇O2(max)) of 76.1% ± 21.1%. The mean age at the time of volume unloading was 2.7 ± 2.4 years, and the mean age at testing was 8.7 ± 2 years. Intermediate staging was performed in 16 of 46 patients (35%). In multivariate analysis, younger age at volume unloading was associated with increased aerobic capacity (p = 0.003). Other variables were not predictive. The subgroup of patients who underwent volume unloading before two years of age achieved a mean percentage predicted V̇O2(max) of 88.6% ± 24.1%. CONCLUSIONS: Preadolescents with single ventricle who undergo volume unloading surgery at an early age demonstrate superior aerobic capacity compared with those whose surgery is delayed until a later age.
Keywords: aerobic capacity; article; clinical article; exercise; Fontan procedure; forced expiratory volume; heart single ventricle; heart stroke volume; human; human cell; human tissue; infant; oxygen consumption; preschool child; priority journal; school child; surgical technique

Managing disagreements in the management of short bowel and hypoplastic left heart syndrome. - Cooper, T.R.; Garcia-Prats, J.A.; Brody, B.A. (Pediatrics, 1999)
BACKGROUND AND OBJECTIVES: When innovative, not yet fully proven therapies are introduced, physicians may have neither experience nor sufficient data in the medical literature to assist in their decision to discuss them with and/or recommend them to patients. Little is known about how physicians deal with this uncertainty. Moreover, when multiple physicians caring for a single patient have reached different conclusions regarding this new therapy, the potential for disagreement exists that could give rise to ethical issues as well as cause confusion to the patient. To explore these topics, we investigated the attitudes of specialists to therapies for two life-threatening diseases: hypoplastic left heart syndrome (HLHS) and short bowel syndrome. METHODS: A forced choice questionnaire was distributed to the heads of neonatology, pediatric cardiology, and pediatric gastroenterology training programs asking about their outcome impressions and treatment recommendations and about the local availability of treatments. In addition, responses from specialists from the same institution were linked in a confidential manner to evaluate the frequency of disagreement within the same institution. Responses were analyzed using chi(2) and Wilcoxon matched pair analysis as appropriate. RESULTS: The overall rate of response was 79%. In institutions that had both neonatology and pediatric gastroenterology training programs, there was a 59% response rate compared with a 73% response rate from institutions that had both neonatology and cardiology programs. Significant differences were noted among specialists as to who would be involved in discussions of therapeutic options with patients in both HLHS and short bowel syndrome. Differences also were noted in the willingness of specialists to discuss and recommend therapies, in the perceived survival and quality of life by various specialists after transplant and palliative surgery, and in the local availability of various options. The neonatologists and gastroenterologists at the same institution disagreed on responses in 34% of the questions with only 1 of the 25 pairs in full agreement. In contrast, the neonatologists and pediatric cardiologists at the same institution disagreed in only 14% of the questions with 7 of the 28 pairs in full agreement. CONCLUSIONS: Substantial disagreement among specialists about new interventions was found. There seem to be fewer differences among specialists when dealing with the more mature therapy, HLHS. Two major ethical issues arise. First, there seems to be no accepted professional standard to which individuals can appeal when determining whether to discuss or recommend new, not-yet-fully-proven technologies. Second, there is the potential for much patient confusion when counseling physicians recommend different options. Colleagues as individuals and specialists as groups should talk to each other before individual discussions with families to ensure that there is a clear understanding of differing beliefs.
Keywords: article; cardiology; comparative study; counseling; decision making; gastroenterology; health personnel attitude; heart transplantation; human; hypoplastic left heart syndrome; neonatology; newborn; palliative therapy; prognosis; public relations; quality of life; questionnaire; short bowel syndrome; total parenteral nutrition

Results after Norwood procedure and subsequent cavopulmonary anastomoses for typical hypoplastic left heart syndrome and similar complex cardiovascular malformations - Breymann, T.; Kirchner, G.; Blanz, U.; Cherlet, E.; Knobl, H.; Meyer, H.; Körfer, R.; Thies, W.-R. (European Journal of Cardio-thoracic Surgery, 1999)
Objective: From October 1989 to June 1998, 60 patients have undergone the Norwood procedure (stage I) at our institution. The results of the staged surgical reconstruction and risk factors were analysed. Typical hypoplastic left heart syndrome (HLHS) and complex lesions with aortic hypoplasia were compared with each other. Patients: Typical HLHS: N=48, median age 15 days (5-190 days), median weight 3.6kg (2.6-5.3kg). Complex lesions (dominant left ventricle): N=12, median age 59 days (10-884 days), median weight 3.4kg (2.4-12kg). Results: Typical HLHS: The stage-I hospital survival was 73% (35/48). It improved from 60% (95% confidence interval: 49-71%) during 1989-1994 to 91% (95% CI: 81-100%) during 1997-1998. Seven patients were lost late. The right ventricular end diastolic diameter (P=0.015), shortening fraction (P=0.027), and the presence of an obstructed pulmonary venous return (P=0.0032) were significant risk factors. 23 children underwent stage-II operation with four (17%) deaths. All survivors experienced an improvement of their statomotoric development. Stage-III operation was performed in 13 patients with no hospital death. Follow up after stage-III procedure was 7 months to 7 years. 4 year actuarial survival, including hospital mortality and deaths at subsequent stages, improved from 28% (95% CI: 18-38%) during 1989-1994 to 58% (95% CI: 48-68%) during 1994-1997. No patient had signs of myocardial insufficiency. Complex lesions: Stage-I hospital survival was 83% (10/12) with no late death. Stage-II was performed in 8 and stage-III in 6 patients with no death respectively. Conclusion: In typical HLHS the results have improved over time. Both size and function of the right ventricle determined significantly stage-I survival. An early operation prevents the natural progression of pulmonary blood flow and may weaken all three risk factors. Patients with complex lesions seemed to have better chances of surviving the early postoperative period. The multistage reconstructions have become a realistic option for patients with HLHS and similar lesions, regardless of the morphologic subtype or diminutiveness of the aorta, and lead to an acceptable quality of life. Copyright (C) 1999 Elsevier Science Ireland Ltd.
Keywords: angiography; arteriovenous shunt; article; cardiovascular malformation; clinical article; Doppler echocardiography; Fontan procedure; heart right ventricle function; heart single ventricle; human; hypoplastic left heart syndrome; infant; lung blood flow; mortality; newborn; priority journal; pulmonary artery; risk factor; superior cava vein; surgical technique; survival

Cyanotic congenital heart disease with decreased pulmonary blood flow in children - Waldman, J.D.; Wernly, J.A. (Pediatric Clinics of North America, 1999)
Of the 'five T's' of cyanotic congenital heart disease-tetralogy of Fallot, TGA, TAPVC, truncus, and tricuspid valve abnormalities (tricuspid atresia, stenosis, and displacement)-the first and last are commonly associated with diminished PBF. The four features that comprise tetralogy of Fallot-right ventricular hypertrophy, VSD, overriding aorta, and subpulmonary stenosis-are all secondary to a single morphogenetic defect: failure of expansion of the subpulmonary conus. This also explains the variability in clinical presentation. When neonates need intervention, shunts are usually performed. Coronary arterial anatomy must be defined before repair, which is usually done after these infants are 3 months of age. Although children with repaired tetralogy of Fallot are not completely 'normal,' markedly increased longevity and improvement in quality of life can be achieved. When major associated defects are present, such as atrioventricular canal defect, diminutive pulmonary arteries or collateral vessels, or left heart lesions, the prognosis changes from excellent to merely good. Tetralogy of Fallot with absent pulmonary valve syndrome is physiologically different from other tetralogy of Fallot conditions and characterized primarily by airway obstruction from massive dilatation of the central and perihilar pulmonary arteries; repair with pulmonary artery reduction is necessary. Tricuspid valve abnormalities include atresia, hypoplasia (i.e., pulmonary atresia with intact ventricular septum), and displacement (i.e., Ebstein anomaly). The pathophysiology that dictates these children's clinical condition (and prognosis) relates to three factors: (1) status of the tricuspid valve, (2) presence and size of a VSD, and (3) TGA or normally related great arteries. Virtually all children with tricuspid valve abnormalities can be palliated; reparative options include repair using two-ventricle, one-ventricle, or 1- 1/2 ventricle repair. Children with critical pulmonary stenosis generally have a normal tricuspid valve and right ventricle. Balloon dilation is usually the only therapy necessary.
Keywords: prostaglandin E1; article; cyanotic heart disease; Ebstein anomaly; echocardiography; electrocardiogram; Fallot tetralogy; Fontan procedure; heart catheterization; interventricular septum; human; pulmonary valve atresia; lung blood flow; pulmonary valve stenosis; right heart hypoplasia; tricuspid valve atresia; tricuspid valve stenosis; vein anastomosis

Hypoplastic left heart syndrome: Duration of survival without surgical intervention - Hoshino, K.; Ogawa, K.; Hishitani, T.; Kitazawa, R.; Uehara, R. (American Heart Journal, 1999)
Background: Mortality rate for heart transplantation for patients with hypoplastic left heart syndrome (HLHS) has improved, but there is a considerable wait until a suitable donor is available. Thus it is important to examine the duration of survival and risk factors for early death in patients with HLHS who did not undergo surgical intervention. Methods and Results: Twenty-six consecutive patients were studied retrospectively. Duration of survival and the 14 following variables were investigated: date of birth, body weight at birth, cardiothoracic ratio, ascending aorta diameter, interatrial communication size, coarctation of the aorta, tricuspid regurgitation, anatomic subtype (patency) of mitral and aortic valve, arterial blood gas findings (pH, PaO2, SaO2, PaCO2, base excess), and ST depression in the electrocardiogram. Twenty patients survived <60 days (group A) and 6 patients survived beyond 60 days (group B). The duration of survival (mean [SD]) was 60 (151) days overall (1 patient is currently alive at 783 days). The long-term survivors (beyond 60 days) increased significantly after 1991 (P < .05). Coarctation of the aorta was a significant risk of early death (<60 days) (P < .05). Interatrial communication size was significantly smaller in group B than in group A (P < .05). The mean pH and base excess were significantly lower in group A than in group B. The other 9 variables showed no significant difference between the 2 groups. Conclusions: There was a significant correlation of long-term survival with stabilized ductal blood flow without coarctation of the aorta, adequate restriction of interatrial communication without severe hypoxemia, and no metabolic acidosis.
Keywords: alkalosis; aortic coarctation; arterial gas; article; blood pH; clinical article; controlled study; female; human; hypoplastic left heart syndrome; infant; male; mortality; newborn; priority journal; risk factor; ST segment depression; survival time

Prostaglandin E1 in infants with congenital heart disease: Indian experience - Saxena, A.; Sharma, M.; Kothari, S.S.; Juneja, R.; Reddy, S.C.B.; Sharma, R.; Bhan, A.; Venugopal, P. (Indian Pediatrics, 1998)
Background: E-type prostaglandins (PGE1) can effectively maintain the patency of the ductus arteriosus in neonates. Its use, therefore can be life saving in infants born with ductus dependent congenital heart disease. Although PGE1 is available for over two decades in western world, it has been introduced in India only since April, 1995. Objective: To assess the efficacy of PGE1 at our center. Setting: Hospital based. Method: 65 infants with ductus dependent congenital heart disease were included. Age at time of starting PGE1 infusion ranged from 18 hours to 39 days. Forty two of these were more than a week of age, 19 were more than 14 days, and two were above one month. PGE1 was started in an initial dose of 0.05 μg/kg/min, decreased to 0.005-0.01 μg/kg/min for maintenance. The indications for use of PGE1 were to increase pulmonary blood flow in 33 cases with pulmonary atresia, tricuspid atresia or critical pulmonic stenosis (Group I); to increase systemic blood flow in 15 cases with coarctation of aorta, hypoplastic left heart and interruption of aortic arch (Group II); to improve mixing in 13 cases of transposition of great arteries (Group III) and for improving the left ventricular volumes by keeping the duct open in 4 cases of transposition of great arteries with intact ventricular septum (Group IV). The efficacy of the drug was assessed by a rise in PaO2 and SaO2% determined for Groups I and III, and by appearance of lower limbs pulses in Group II. Left ventricular volumes were serially measured by echocardiography in Group IV cases. Results: The drug was successful in 62 of the 65 cases. There were two failures. One was a 39 days old baby with Ebstein's anomaly of tricuspid valve and pulmonary atresia and other was an eight days old baby with coarctation of aorta and renal failure. In addition, PGE1 could not be continued in another baby due to development of a linear skin rash locally. Side effects included apnea in 5 (9%) of 56 spontaneously breathing patients. Necrotizing enterocolitis, hyperpyrexia and jitteriness was seen in one case each. Six patients died. Two were related to PGE1 one due to failure, another due to its side effects. Definitive procedure were performed in 51 cases electively. PGE1 was used upto 13 days with sustained benefit. Conclusion: PGE1 is an effective drug for keeping the ductus open in infants with ductus dependent congenital heart disease. It can be used for neonates beyond the first week of life with efficacy. Apnea is a major side effect and close monitoring is essential.
Keywords: prostaglandin E1; aortic arch interruption; aortic coarctation; apnea; article; congenital heart disease; drug efficacy; drug indication; female; great vessels transposition; heart left ventricle volume; human; hyperpyrexia; hypoplastic left heart syndrome; India; infant; intravenous drug administration; pulmonary valve atresia; lung blood flow; major clinical study; male; necrotizing enterocolitis; nervousness; newborn; patent ductus arteriosus; pulmonary valve stenosis; rash; tricuspid valve atresia; prostin vr

Early developmental outcome after the norwood procedure for hypoplastic left heart syndrome - Kern, J.H.; Hinton, V.J.; Nereo, N.E.; Hayes, C.J.; Gersony, W.M. (Pediatrics, 1998)
Objective. To assess intellect and adaptive behavior in children with hypoplastic left heart syndrome (HLHS) who had undergone at least two surgical stages of the Norwood procedure. Methods. Fourteen children with HLHS > 3 years of age participated in the study. The patients underwent intelligence quotient (IQ) testing, and their parents were interviewed regarding their children's adaptive behavior. Results were compared with those of 10 family controls. Outcomes were studied for possible correlation with perioperative variables. Results. Among the HLHS patients, the median scores for full scale IQ and adaptive behavior were 88 and 91, respectively (normal = 100 ± 15). One child met criteria for mental retardation. Family controls scored generally higher than did HLHS patients, but only differences in adaptive behavior were statistically significant. A negative correlation was found between stage I circulatory arrest time and full scale IQ. Conclusions. Children with HLHS most often function in the low-normal range of intelligence and adaptive behavior. A prolonged circulatory arrest time may result in decreased intellectual function.
Keywords: adaptation; article; clinical article; controlled study; early diagnosis; female; heart arrest; human; human cell; human tissue; hypoplastic left heart syndrome; intelligence quotient; intelligence test; male; mental development; mental retardation malformation syndrome; outcomes research; preschool child; priority journal; risk factor

Alterations in pulmonary artery flow patterns and shear stress determined with three-dimensional phase-contrast magnetic resonance imaging in Fontan patients - Morgan, V.L.; Graham T.P., Jr.; Roselli, R.J.; Lorenz, C.H. (Journal of Thoracic and Cardiovascular Surgery, 1998)
Objective: This study compares in vivo pulmonary blood flow patterns and shear stresses in patients with either the direct atrium-pulmonary artery connection or the bicaval tunnel connection of the Fontan procedure to those in normal volunteers. Comparisons were made with the use of three-dimensional phase contrast magnetic resonance imaging. Methods: Three-dimensional velocities, flows, and pulmonary artery cross-sectional areas were measured in both pulmonary arteries of each subject. Axial, circumferential, and radial shear stresses were calculated with the use of velocities and estimates of viscosity. Results: The axial velocities were not significantly different between subject groups. However, the flows and cross-sectional areas were higher in the normal group than in the two patient groups in both pulmonary arteries. The group with the bicaval connection had circular swirling in the cross section of both pulmonary arteries, causing higher shear stresses than in the controls. The disorder caused by the connection of the atrium to the pulmonary artery caused an increase in some shear stresses over the controls, but not higher than those found in the group having a bicaval tunnel. Conclusions: We found that pulmonary flow was equally reduced compared with normal flow in both patient groups. This reduction in flow can be attributed in part to the reduced size of the pulmonary arteries in both patient groups without change in axial velocity. We also found higher shear stress acting on the wall of the vessels in the patients having a bicaval tunnel, which may alter endothelial function and affect the longevity of the repair.
Keywords: adolescent; adult; article; blood vessel wall; child; clinical article; congenital heart disease; controlled study; female; Fontan procedure; heart single ventricle; human; lung blood flow; male; nuclear magnetic resonance imaging; priority journal; shear stress; surgical technique; three-dimensional imaging; tricuspid valve atresia; Siemens Magneton SP 4000 scanner

Nonmalignant hyperthermia on induction of anesthesia in a pediatric patient undergoing Bi-directional glenn procedure - Leung, W.K.; Jahr, J.S.; Hotz, J.; Pollock, M. (Journal of Clinical Anesthesia, 1998)
We report a case of severe hyperthermia in a 6-month-old boy with a single ventricle, dextrocardia, asplenia, and transposition of the great arteries, during induction of anesthesia on three separate occasions. To our knowledge, this is the first case reported of repeated intraoperative hyperthermia not related to malignant hyperthermia, infection, neuroendocrine tumor, or iatrogenic causes (e.g., anticholinergic blockade or warming devices). The severe hyperthermia may be secondary to the medications given before and during induction and/or the stress of the induction. Among the induction medications given during the three episodes, fentanyl is the most likely contributing drug. Human data indicate that opioids increase the sweating threshold and decrease the vasoconstriction and shivering thresholds. The medications could cause a widening in the thermoregulation interthreshold and the stress could induce nonshivering thermogenesis.
Keywords: acetylsalicylic acid; altizide plus spironolactone; amoxicillin; anesthetic agent; cefuroxime; digoxin; erythromycin; etomidate; fentanyl; furosemide; methylprednisolone; midazolam; neuromuscular blocking agent; pancuronium; paracetamol; rocuronium; sulfafurazole; anesthesia complication; anesthesia induction; article; cardiovascular disease; case report; chronic otitis media; congenital heart disease; general anesthesia; human; hyperthermia; infant; inhalational drug administration; intraoperative period; intravenous drug administration; male; pediatric anesthesia; pediatric surgery; priority journal; respiratory tract infection; surgical stress; thermogenesis

Total cavopulmonary anastomosis (Fontan) in children with Down's syndrome - Campbell, R.M.; Adatia, I.; Gow, R.M.; Webb, G.D.; Williams, W.G.; Freedom, R.M. (Annals of Thoracic Surgery, 1998)
Background. There is a paucity of information to guide the management of the child with Down's syndrome and congenital heart disease in whom biventricular repair is precluded. Methods. Through the cardiology and cardiovascular surgery databases of The Hospital for Sick Children and Toronto Congenital Cardiac Centre for Adults, we identified patients with trisomy 21 and ventricular hypoplasia who had undergone a Fontan procedure (or modification). Results. Of 533 patients who had undergone a Fontan operation between 1976 and 1997, 4 had trisomy 21. All 4 patients had unbalanced complete atrioventricular septal defect with right ventricular hypoplasia in 3 and left ventricular hypoplasia in 1. Three patients survived, and 1 died of endocarditis. The 3 survivors have done well in the short term and medium term without complications related to the pulmonary vasculature. Conclusions. We suggest that in appropriately selected patients with trisomy 21 and ventricular hypoplasia who are unsuitable for two or one and a half ventricle repair, the Fontan procedure is not contraindicated and provides short, term and medium-term benefit.
Keywords: article; case report; child; congenital heart disease; Down syndrome; endocarditis; Fontan procedure; heart atrium septum defect; human; hypoplastic left heart syndrome; lung artery banding; priority journal; treatment outcome; trisomy 21

Hypoplastic left heart syndrome: "Which is the best operative strategy?". - Hehrlein, F.W.; Yamamoto, T.; Orime, Y.; Bauer, J. (Annals of thoracic and cardiovascular surgery : official journal of the Association of Thoracic and Cardiovascular Surgeons of Asia, 1998)
Therapy for the hypoplastic left heart syndrome (HLHS) is still under debate. We report about our experience in the treatment of this cardiac malformation using heart transplantation and Norwood palliation. From 1988 to 1997 a total number of 30 infants with hypoplastic left heart underwent heart transplantation. Mean age at transplantation was 66 days. Mean waiting time was 53 days. Donor-recipient weight ratio ranged from 0.6 to 3.9. There were 6 early hospital deaths and one late death until now. Causes of death were rejection (3), right heart failure (2), infection (1) and multi system organ failure (1). Overall survival was 77%. Increasing experience improved results substantially. From 1988 to 1993 (n=12) survival rate was 58%, whereas from 1994 to 1997 (n=18) survival rate increased to 88%. Quality of life is excellent in the 23 surviving infants. Only one infant shows severe morbidity (neurological defect). The Norwood procedure has been performed in 18 patients since 1993. Five patients died after the first stage. Up until now 10 infants have undergone the second stage and one infant the third stage procedure. None of them have died. Survival rate is 72% for the whole group. Taking into account that 12 infants died on the waiting list for transplanatation (28%), we have comparable results in terms of the survival rate for transplantation and the Norwood procedure in infants with HLHS since 1994. However quality of life and physical development are far better in infants after transplantation according to our experience. Therefore we prefer, whenever possible heart transplantation in the treatment of hypoplastic left heart syndrome. Certainly not all infants with this malformation can undergo transplantation because of the lack of donor organs. Criteria for the decision regarding the operative strategy in our opinion are function of the right ventricle and tricuspid valve, size of the interaterial communication and parental request.
Keywords: angiocardiography; article; comparative study; donor; follow up; graft rejection; heart surgery; heart transplantation; hospital admission; human; hypoplastic left heart syndrome; infant; methodology; mortality; newborn; palliative therapy; postoperative complication; radiography; retrospective study; risk factor; survival rate

Abnormal dynamic cardiorespiratory responses to exercise in pediatric patients after fonton procudure - Troutman, W.B.; Barstow, T.J.; Galindo, A.J.; Cooper, D.M. (Journal of the American College of Cardiology, 1998)
Objectives. Novel protocols were used to focus on dynamic cardiorespiratory function during submaximal exercise and on the recovery from 1-min pulses of exercise in children who had undergone Fontan corrections for single-ventricle lesions. Background. Particularly in children, maximal oxygen uptake (Vo2max), which is commonly used to assess the functional capability of patients after the Fontan procedure, is highly effort dependent and not physiologic and leads to uncomfortable metabolic and cardiorespiratory stress. Alternative approaches include the measurement of dynamic responses during progressive exercise and recovery after short bursts of exercise. These strategies yield mechanistic insight into cardiorespiratory impairment and can be used to gauge limitations in daily life activity. Methods. Sixteen patients (mean (±SD) age 12.2.± 2.4 years; 9 boys) and 10 age-matched control subjects (mean age 12.2 ± 2.4 years; 6 boys) performed two separate cycle ergometer test in which gas exchange was measured on a breath by basis:1) Progressive exercise was used to determine the dynamic relation among Vo2, carbon dioxide production (VCO2), ventilation (VE), heart rate (HR) and work rate (WR).2) A 1-min constant WR test was used to determine the recovery time for gas exchange and HR. Results. Peak VO2 and anaerobic threshold were reduced in patients who underwent the Fontan procedure compared with control subjects by 57% and 52%, respectively (p < 0.001). Dynamic relations during progressive exercise - ΔVO2/ΔHR and ΔVO2/ΔWR - were decreased (p < 0.001) and ΔE/ΔVCO2 was increased (p < 0.005) in the Fontan group patients. Recovery times for HR VO2 were prolonged in the Fontan group patients by 154% and 69%, respectively (p < 0.01). Conclusions. The results demonstrate that submaximal gas exchange response to progressive exercise and recovery times after brief intensity exercise are abnormal in patients after the Fontan procedure. These observations complement the findings of reduced VO2 max observed here and by others. We speculate that the mechanisms for these responses are related to 1) a pervasive reduction in stroke volume for both low and high intensity exercise, 2) an abnormal linkage of ventilation to tissue carbon dioxide production, and 3) increased dependence on anaerobic metabolism in skeletal muscles. The prolonged recovery of HR and VO2 provides a possible mechanism for reduced physical activity.
Keywords: anaerobic threshold; article; bicycle ergometry; clinical article; exercise test; female; follow up; Fontan procedure; heart single ventricle; human; lung gas exchange; male; oxygen tension; priority journal; school child; treatment outcome

Clinical implications of isolated double aortic arch and its complex with intracardiac anomalies - Lee, M.-L.; Wang, J.-K.; Wu, M.-H.; Lue, H.-C.; Ing-Sh Chiu,; Chang, C.-I. (International Journal of Cardiology, 1998)
From July 1, 1989 to June 30, 1996, a total of six patients, four male and two female, with double aortic arch (DAA) were registered. They aged 16 days to 6.5 years. There were two patients with isolated DAA, and four complicated with intracardiac anomalies. All six patients presented respiratory distress and feeding problem early in life. However, cyanosis, owing to decreased pulmonary blood flow, predominated the clinical picture in each patient having DAA intricated with tetralogy of Fallot (TOF) and pulmonary stenosis, TOF with absent pulmonary valve syndrome, and type II-A tricuspid atresia. DiGeorge syndrome was documented in one patient with TOF and pulmonary stenosis. Expiratory wheezing was remarkable in the patient with TOF and absent pulmonary valve syndrome. Mild cyanosis and heart failure was noted in one patient with ventricular septal defect (VSD), and bicuspid pulmonary valve with mild valvular stenosis. Barium esophagogram showed indentations on esophagus in five patients. Echocardiography was yielding in three infants. Four patients, two isolated and two complex DAA, survived the surgical division of the smaller left aortic arch. One-stage and two-stage operation was performed in patients having DAA intricated with VSD and TOF, respectively. The other two patients with complex DAA remained in close observation owing to the tolerance of symptoms related to intracardiac anomalies.
Keywords: aortic arch anomaly; article; child; clinical article; clinical feature; congenital heart malformation; cyanosis; DiGeorge syndrome; echocardiography; esophagography; Fallot tetralogy; feeding disorder; female; heart failure; heart ventricle septum defect; human; infant; male; newborn; priority journal; pulmonary valve stenosis; respiratory distress; tricuspid valve atresia; wheezing

Outcome after prenatal diagnosis of the hypoplastic left heart syndrome - Allan, L.D.; Apfel, H.D.; Printz, B.F. (Heart, 1998)
Objective - To derive accurate survival figures in the current surgical era for counselling in early pregnancy after the diagnosis of fetal hypoplastic left heart syndrome. Setting - A tertiary referral centre for paediatric cardiology and cardiac surgery. Design - A retrospective study of the outcome in all cases of hypoplastic left heart syndrome presenting in fetal life between mid-1993 and the end of 1996. Patients - The diagnosis was made in 30 fetuses. In four of 12 identified before 24 weeks' gestation the mothers chose to terminate the pregnancy. There was an intention to treat in 24 of the remaining fetuses. Main outcome measure - Survival to six months of postnatal life. Results - Of the 24 infants, five were not offered Norwood stage I because of trisomy 18 (n = 2), unfavourable cardiac anatomy (n = 2), or neurological impairment (n = 1). One further infant did not survive to cardiac surgery after gastrointestinal surgery. Of the remaining 18 patients, eight had features that were considered to increase the risk of surgical repair. Of the 18 patients who underwent Norwood stage 1, there were nine survivors. There was a survival rate of 70% in infants undergoing surgery with no complicating features, a 50% survival of the all surgical candidates, and 37.5% survival from an intention to treat position. Conclusions - At the initial diagnosis of fetal hypoplastic left heart syndrome, the overall survival appears to be less than 40%. Evaluation must include detailed extracardiac and intracardiac assessment to predict the risks of surgical treatment. Prenatal counselling can be modified as pregnancy advances, depending on the detection or exclusion of complicating factors.
Keywords: article; clinical article; counseling; echocardiography; fetus; first trimester pregnancy; human; hypoplastic left heart syndrome; infant; outcomes research; prenatal diagnosis; priority journal; quality of life; retrospective study; survival

Bidirectional cavo-pulmonary anastomosis with an additional flow source to the lungs: Clinical experience in 21 cases - Borini, I.; Marasini, M.; Dalmonte, P.; Bava, G.L.; Lerzo, F.; Cervo, G.; Moretti, R.; Bertolini, A.; Zannini, L. (Cardiovascular Surgery, 1997)
The Fontan operation is considered a palliative procedure for the treatment of complex congenital heart diseases with a morbidity and mortality that are not negligible, expecially in high-risk patients. In these cases, a bidirectional cavopulmonary anastomosis with additional source of blood flow to the lungs can represent a valuable surgical option. Between November 1992 and December 1995, 21 patients with univentricular heart physiology were submitted to bidirectional cavopulmonary anastomosis with additional blood flow the additional flow consisted of an aortopulmonary shunt in 13 cases, pulmonary artery banding in seven cases, and pulmonary artery stenosis in one case. Mean age at operation was 35.5 months (range 4 months to 12 years) and mean body weight 10.9 (range 4-24.4) kg. Hospital mortality was zero. Morbidity (pleuropericardial effusions) was significant in one case. There were three late deaths (14%) caused by worsening atrioventricular valve regurgitation: two of these occurred in patients with right isomerism. Late haemodynamic evaluation documented a significant increase in cardiac output (P < 0.01) and oxygen saturation (P < 0.05) during pharmacological stress testing. Angiographic characterization of blood flow distribution to the lungs showed better results when the additional blood flow was represented by an anterograde source (pulmonary artery banding or native pulmonary artery stenosis). In conclusion, bidrectional cavopulmonary anastomosis with additional blood flow is a good alternative to classic or fenestrated Fontan technique in high-risk patients. Secondly, the diagnosis of isomerism could be a contraindication to this type of surgery, because the persistent volume overload could worsen atrioventricular valve regurgitation. Thirdly, the pharmacological stress testing shows a favourable behaviour of cardiac output and arterial oxygen saturation. Fourth, the type of additional blood flow seems to condition both pulsatility and distribution of pulmonary blood flow.
Keywords: anastomosis; article; child; clinical article; clinical trial; congenital heart disease; Fontan procedure; hemodynamics; human; infant; lung blood flow; mortality; priority journal; pulmonary artery; superior cava vein; surgical technique

Pulmonary atresia with intact septum: Findings on exercise stress sestamibi scan - Fisher, D.J.; Ferency, S.L.; Rosenbaum, D.M.; McCloskey, J.P. (Clinical Nuclear Medicine, 1997)
Right ventricular size in cases of pulmonary atresia is determined by blood flow into and out of the right ventricle. A hypoplastic or enlarged right ventricle can result. In cases of an intact septum, elevated right ventricular pressure results in retrogated flow of blood from a blind-ending right ventricle into the coronary artery circulation via enlarged myocardial sinusoids. In some cases, no connection exists between the coronary arteries and the aorta. Stress sestamibi myocardial perfusion scan is helpful in determining if myocardium is at risk for ischemia or infarction in cases in which coronary circulation is influenced by right ventricular-coronary artery communications.
Keywords: methoxy isobutyl isonitrile technetium tc 99m; adolescent; angiocardiography; article; case report; coronary artery blood flow; Fontan procedure; heart infarction; heart muscle ischemia; heart right ventricle hypertrophy; heart scintiscanning; interventricular septum; human; pulmonary valve atresia; male

Survival and risk factors for death after cardiac transplantation in infants: A multi-institutional study - Canter, C.; Naftel, D.; Caldwell, R.; Chinnock, R.; Pahl, E.; Frazier, E.; Kirklin, J.; Boucek, M.; Morrow, R. (Circulation, 1997)
Background: Despite the increasing application of cardiac transplantation in infants, reported survival rates vary, and risk factors for death are poorly understood. Methods and Results: To examine early survival and risk factors for death in infants (<1 year of age) undergoing cardiac transplantation, 141 infants (36 < 1 month of age) underwent primary cardiac transplantation between January 1, 1993, and January 1, 1995, at 23 centers in the Pediatric Heart Transplant Study (PHTS). Diagnoses were hypoplastic left heart syndrome (66%), other congenital hearth disease (17%), cardiomyopathy (14%), and other (3%). Actuarial survival after cardiac transplantation was 84% at 1 month, 70% at 1 year, and 69% at 2 years, with the greatest hazard for death within the first 3 months. The principal cause of death was early graft failure in 20 patients (52% of deaths), infection in 10 (26% of deaths), and rejection in 4 (10%). On the basis of multivariate analysis, risk factors for early mortality were history of previous sternotomy (P=.0003), nonidentical blood type donor (P=.01), recipient non- blood group A (P=.02), and donor cause of death other than closed head trauma (P=.04). Diagnosis at listing, waiting time (mean, 1.3 months), graft ischemic time (mean, 228 minutes; range, 68 to 479 minutes), and recipient ventilatory or inotropic support at listing were not predictive for mortality after transplant. Conclusions: The higher mortality rate observed with infant heart tranplantation is due to a higher mortality within the first month after transplantation as a result of early graft failure. Strategies to improve donor heart function at implantation would have the greatest impact on survival after infant cardiac tranplantation.
Keywords: article; graft failure; heart death; heart transplantation; human; infant; major clinical study; newborn; postoperative complication; priority journal; risk assessment; risk factor

Operative mortality and frequency of coexistent anomalies in interruption of the aortic arch - Powell, C.B.; Stone, F.M.; Atkins, D.L.; Watson, D.G.; Moller, J.H. (American Journal of Cardiology, 1997)
Keywords: aortic arch interruption; aortopulmonary septal defect; article; DiGeorge syndrome; Down syndrome; Goldenhar syndrome; great vessels transposition; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; human; infant; major clinical study; mitral valve atresia; patent ductus arteriosus; priority journal; surgical approach; surgical mortality; tricuspid valve atresia; United States; Williams Beuren syndrome

The death of an innocent. - Fontanilla Jr., L. (Hawaii medical journal, 1997)
Keywords: article; decision making; female; human; hypoplastic left heart syndrome; medical ethics; newborn; patient advocacy; professional-patient relationship; religion; Religious Approach; right to die; treatment refusal

Epidural anesthesia for emergency caesarean section in a patient with single ventricle and aortic stenosis. - Peng, T.C.; Chuah, E.C.; Tan, P.P. (Acta anaesthesiologica Sinica, 1997)
A 24-year-old parturient with single ventricle and moderate aortic stenosis was admitted due to preeclampsia and fetal distress at 31 weeks' gestation. Emergency Caesarean section was performed under lumbar epidural anesthesia and epidural analgesia was given for post-operative pain control. Mother and baby both survived. The anesthetic techniques and managements in other parturients with similar congenital cardiac anomalies are also reviewed and described.
Keywords: adult; aortic valve stenosis; article; case report; cesarean section; congenital malformation; epidural anesthesia; female; heart ventricle; human; male; newborn; obstetric anesthesia; pathophysiology; pregnancy; pregnancy complication

Complete atrioventricular septal defects: the influence of associated cardiac anomalies on surgical management and outcome. - Redmond, J.M.; Silove, E.D.; De Giovanni, J.V.; Wright, J.G.; Sreeram, N.; Brawn, W.J.; Sethia, B. (European journal of cardio-thoracic surgery : official journal of the European Association for Cardio-thoracic Surgery, 1996)
OBJECTIVE: Major associated cardiac anomalies are known to increase the risk of repair of complete atrioventricular septal defects (CAVSDs). The purpose of this study was to examine the effects of such anomalies on the current surgical management of CAVSDs and their influence on outcome following repair. METHODS: We performed a retrospective review of a 100 consecutive non-isomeric patients undergoing repair of CAVSD at our institution, between January 1989 and December 1994; patients with partial or intermediate defects were excluded. Complete atrioventricular septal defect patients with other major cardiac abnormalities (complex) were then compared to those with isolated CAVSDs. RESULTS: There were 15 patients (15%) with associated anomalies; 3 had tetralogy of Fallot, 1 patient had pulmonary atresia, 6 had hypoplastic left or right ventricle, 1 had tetralogy of Fallot and hyperplastic right ventricle, 2 patients had double outlet right ventricle, 1 had hypoplastic aortic arch and 1 patient had aortic coarctation. The median age at operation was similar for both groups (4.2 months), while the median weight was not significantly different for isolated CAVSDs compared to complex (4.2 months vs 3.4 months, P = 0.89), but there was a higher incidence of trisomy 21 (70/85, 82% vs 8/15, 53.3%, P = 0.01). Two of the 85 isolated CAVSD patients (2.3%) had undergone palliative pulmonary artery banding, while 5 of the 15 complex patients (33.3%) had either banding or Blalock-Taussig shunts performed. The technique of CAVSD repair was identical in each group. All complex patients had standard repair of their associated anomalies. Hospital mortality was higher in the complex group (3/15, 20% vs 2/85, 2.3%, P = 0.004); all early deaths in the complex group occurred in patients with a hypoplastic ventricle. Reoperation for left atrioventricular valve regurgitation was required in six isolated CAVSD patients (7.1%) and in one complex (6.6%). CONCLUSIONS: In the absence of significant ventricular hypoplasia, the early results of surgical repair in patients with CAVSDs and associated cardiovascular anomalies are similar to those achieved in patients with isolated CAVSD.
Keywords: aortic coarctation; article; child; congenital malformation; Down syndrome; endocardial cushion defect; Fallot tetralogy; female; heart right ventricle double outlet; human; hypoplastic left heart syndrome; infant; male; mortality; preschool child; pulmonary artery; reoperation; retrospective study; survival rate; procedures; thoracic aorta; treatment outcome

Noninvasive evaluation of aortic valve anatomy - Sanders, S.P.; Simonds, H.M.; Jameson, S.M. (Echocardiography, 1996)
Although aortic valve anatomy is three-dimensionally complex, careful echocardiographic investigation can yield surgically relevant information. The promise of intravascular and transesophageal imaging is in yielding the raw data of sufficient resolution to make the three-dimensional reconstruction clinically meaningful.
Keywords: aortic valve disease; aortic valve prolapse; aortic valve stenosis; article; child; color Doppler flowmetry; Doppler echocardiography; human; hypoplastic left heart syndrome; image reconstruction; infant; Marfan syndrome; priority journal; three-dimensional imaging; Williams Beuren syndrome

Myocardial dysfunction and depressed fatty acid metabolism in patients with cyanotic congenital heart disease - Kondo, C.; Nakazawa, M.; Kusakabe, K.; Momma, K. (Journal of Nuclear Cardiology, 1996)
Background. Myocardial contractile dysfunction has been frequently observed in adolescents or adults with cyanotic congenital heart disease. Impaired energy metabolism may be present in such dysfunctional myocardium. Methods and Results. To evaluate the findings of myocardial free fatty acid metabolism, and its relations to ventricular wall motion and myocardial perfusion in cyanotic congenital heart disease, we performed a combined study of iodine 123-labeled 15-(p-iodophenyl)3- (R,S)-methylpentadecanoic acid (BMIPP) scintigraphy, thallium scintigraphy, and contrast cineangiography in seven patients with single right or left ventricle. The results showed that wall motion was reduced in 17 of 35 ventricular segments (49%), which were mostly identical in location to decreased BMIPP uptake. The severity of BMIPP uptake deficit correlated positively with the degree of impairment of wall motion. On the other hand, thallium uptake was abnormal only in 5 of 35 segments (14%), and the severity of the perfusion defect did not correlate with the degree of wall motion abnormality. Conclusions. Contractile dysfunction in cyanotic heart disease was primarily linked to impaired free fatty acid metabolism rather than to myocardial scar as represented by perfusion defect on thallium imaging.
Keywords: decanoic acid derivative; iodine 123; thallium; adolescent; adult; article; child; clinical article; cyanotic heart disease; fatty acid metabolism; female; heart cineventriculography; heart contraction; heart muscle metabolism; heart perfusion; heart scintiscanning; heart single ventricle; human; human tissue; male; priority journal

No heroics, just love. (Midwifery today and childbirth education, 1996)
Keywords: article; attitude to death; case report; female; home delivery; human; hypoplastic left heart syndrome; male; mother; newborn; nurse midwife; nursing; pregnancy; psychological aspect

Physiology, diagnosis and clinical profile of the hypoplastic left heart syndrome - Rosenthal, A. (Progress in Pediatric Cardiology, 1996)
Whereas multiple and different cardiac abnormalities may be accompanied by hypoplasia of the left heart, the postnatal pathophysiologic changes which accompany these abnormalities are very similar. In the fetus, hypoplasia of the left ventricle does not result in any complications, but the post-natal physiologic changes lead to severe hemodynamic and circulatory complications which in the absence of treatment are fatal. The major physiologic changes are those related to the decrease in pulmonary vascular resistance, spontaneous constriction or closure of the ductus arteriosus, and restriction of the obligatory left-to-right shunt which must exist through an interatrial communication. The clinical features are closely related to the dominance and severity of the physiologic changes and the balance between the systemic and pulmonary vascular resistance. Presentation may be with respiratory distress, congestive heart failure, vascular collapse, or less frequently with severe cyanosis. The presence of mild hypoxemia, normal or reduced Pace, and very low pH are characteristic features of infants with hypoplastic left heart syndrome. Early post-natal detection of these infants may be enhanced by screening all newborns discharged from the nursery with measurement of systemic arterial oxygen saturations by a pulse volume oximeter.
Keywords: arterial oxygen saturation; clinical feature; collapse; congestive heart failure; cyanosis; ductus arteriosus; early diagnosis; heart hemodynamics; human; hypoplastic left heart syndrome; hypoxemia; lung vascular resistance; newborn; pathophysiology; perinatal period; pH; priority journal; pulse oximetry; respiratory arrest; screening; short survey

Mid-term results of the modified Senning operation for cavopulmonary connection with autologous tissue. - Benatar, A.; Tanke, R.; Roef, M.; Meyboom, E.J.; Van de Wal, H.J. (European journal of cardio-thoracic surgery : official journal of the European Association for Cardio-thoracic Surgery, 1995)
The aim of this study was to determine the results and mid-term outcome of a modified Senning technique using autologous tissue for total cavopulmonary connection. The study involved 31 children, 8 with tricuspid atresia and 23 with complex congenital heart disease. In this operation, a flap of autologous atrial free wall tissue was used to tunnel inferior vena caval blood to the pulmonary arteries. An additional Damus-Kay-Stansel operation was required in 9 patients with subaortic obstruction. Results: the early mortality rate was 16% (5 out of 31 patients) and there were four late deaths. Complications: Pleural effusions were encountered in 17 patients, of whom 4 had a concomitant pericardial effusion. Diaphragmatic paralysis was diagnosed in five patients, one of whom underwent surgical plication. Median hospital stay was 26 days. The 1- to 5-year actuarial survival was 68.6%. Follow-up ranged from 10 months to 7.1 years, mean 3.2 years. A serious atrial arrhythmia was diagnosed in one patient and another one died, possibly from rhythm disorders. Exercise tolerance and quality of life has improved in all but one of the survivors. Although follow-up is short, we have thus far witnessed a low incidence of hemodynamic and rhythm disturbances with this modification of the cavopulmonary connection.
Keywords: adolescent; anastomosis; article; child; congenital heart malformation; congenital malformation; diaphragm paralysis; female; follow up; Fontan procedure; heart arrhythmia; heart atrium; human; infant; inferior cava vein; length of stay; male; methodology; pericardial effusion; plastic surgery; pleura effusion; postoperative complication; preschool child; pulmonary artery; statistical analysis; survival rate; tricuspid valve

Determinants of survival in pediatric continuous hemofiltration - Smoyer, W.E.; McAdams, C.; Kaplan, B.S.; Sherbotie, J.R. (Journal of the American Society of Nephrology, 1995)
Continuous hemofiltration (CH) is being used in increasing numbers of pediatric intensive care unit patients. Experience with 114 CH treatments in 98 critically ill children from March 1988 to March 1993 is presented in this study. Ages ranged from 1 day to 23 yr (mean ± SE = 7.1 ± 0.7 yr), and 54% of patients were male. Seventeen percent of all treatments were performed in neonates under 1 month of age. The most common primary diagnoses were sepsis and adult respiratory distress syndrome (11 patients each), liver transplantation and hypoplastic left heart syndrome (10 patients each), and hemolytic uremic syndrome (9 patients). The most frequent indications for CH were fluid overload and acute renal failure (42% each). Choices for CH included: continuous arteriovenous hemofiltration (CAVH, 50%), continuous arteriovenous hemodiafiltration (CAVH-D, 23%), continuous venovenous hemofiltration (CVVH, 18%), and continuous venovenous hemodiafiltration (CVVH-D, 9%). Choices for anticoagulation included: none (47%), regional (49%), and systemic (4%). Treatment duration ranged from 1 to 25 days (mean = 5.3 ± 0.4 days). Mean filter life span for 363 filters was 0.94 ± 0.1 filters/patient per day. Despite an overall survival rate of 43%, survival to discharge varied greatly (0 to 100%) among the 24 diagnostic groups: tumor lysis syndrome and systemic lupus erythematosus (3/3 patients each, 100%) hemolytic uremic syndrome (8/9 patients, 89%). This compares with: bone marrow transplantation (0/16 patients, 0%), hypoplastic left heart syndrome (2/10 patients, 20%), and leukemia (1/4 patients, 25%). Survival to hospital discharge was better in patients who did not receive pressors (P < 0.005) and in patients treated with combined ultrafiltration and dialysis (CAVH-D, CVVH-D) compared with ultrafiltration alone (CAVH, CVVH) (P < 0.005), but was not notably affected by patient age, sex, use of anticoagulation, filter life span, blood pump-assisted versus spontaneous CH, or duration of therapy. Filter life span was not affected by use of anticoagulation, but was remarkably longer in patients with arteriovenous versus venovenous CH (P < 0.004). It was concluded that: (1) empirical anticoagulation of patients treated with CH is not necessary; (2) children with a minority of underlying diseases and those requiring pressor support at initiation of CH appear to have relatively poor survival rates despite the technically effective use of CH; and (3) the addition of countercurrent dialysis to routine CH may enhance patient survival to hospital discharge.
Keywords: adolescent; adult; anticoagulation; article; child; female; hemodialysis; hemofiltration; human; infant; major clinical study; male; newborn; priority journal; survival

Incidence of congenital heart disease: I. Postnatal incidence - Hoffman, J.I.E. (Pediatric Cardiology, 1995)
The incidence of congenital heart disease (CHD) in the Western industrialized world has varied from a low value of about 3 to 5 per 1000 live births to about 12 per 1000 live births. Most of the lower incidence figures were obtained before there were sufficiently well trained pediatric cardiologists and before the success of cardiac surgery put a premium on early and correct diagnosis of CHD. The advent of echocardiography with Doppler color flow measurements has made it possible to diagnose lesions that are asymptomatic, minor, and even without murmurs. Given these differences, there does not appear to have been a significant increase in the incidence of CHD over the last 20-30 years. The incidence of CHD in underdeveloped countries is not known, but the distribution of different lesions is fairly similar to those in developed countries except perhaps for fewer with aortic stenosis and coarctation of the aorta.
Keywords: aortic coarctation; aortic valve stenosis; aortopulmonary septal defect; article; child; congenital heart disease; diagnostic accuracy; Down syndrome; ethnic difference; Fallot tetralogy; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; heart ventricle septum defect; human; hypoplastic left heart syndrome; incidence; infant; lung vein drainage anomaly; major clinical study; patent ductus arteriosus; preschool child; pulmonary valve stenosis; trisomy 21

Neurodevelopmental outcome of infants with hypoplastic left heart syndrome - Rogers, B.T.; Msall, M.E.; Buck, G.M.; Lyon, N.R.; Norris, M.K.; Roland, J.-M.A.; Gingell, R.L.; Cleveland, D.C.; Pieroni, D.R. (Journal of Pediatrics, 1995)
The neurodevelopmental outcome of hypoplastic left heart syndrome in infants remains unclear. All 11 survivors of staged surgical repair of hypoplastic left heart syndrome received standardized neurodevelopmental assessments at one regional children's hospital. Seven children (64%) had major developmental disabilities. Quality-of-life outcomes must be considered when management options for children with hypoplastic left heart syndrome are evaluated.
Keywords: article; clinical article; cognition; developmental disorder; disability; human; hypoplastic left heart syndrome; newborn; priority journal; prognosis; quality of life

Comparison of cardiopulmonary adaptation during exercise in children after the atriopulmonary and total cavopulmonary connection Fontan procedures - Rosenthal, M.; Bush, A.; Deanfield, J.; Redington, A. (Circulation, 1995)
Background: There are several potential physiological differences between the atriopulmonary (AP) and the total cavopulmonary connection (TCPC) Fontan circulations. Studies suggest that the TCPC reduces energy loss due to turbulence and may have more dependence on respiratory movement for pulmonary blood flow. We compared cardiopulmonary physiology during rest and exercise in patients who had undergone the AP Fontan procedure with those who had undergone the TCPC Fontan procedure. Methods and Results: Forty-three children were studied more than 6 months after undergoing a Fontan procedure (23 AP and 20 TCPC); 106 healthy children were also studied as a control group. Measurements of effective pulmonary blood flow, stroke volume, arteriovenous oxygen difference, minute ventilation, heart rate, and oxygen and carbon dioxide consumption were made with an Innovision quadrupole mass spectrometer. Data from the control group allowed calculation of z scores for the Fontan groups matched for age, sex, pubertal stage, and body surface area. Maximal exercise performance was equal in the two Fontan groups, but it was below normal. However, adaptation to exercise was different in the Fontan groups. After 9 minutes of exercise, pulmonary blood flow rose less in the AP group than in the TCPC group (P<.01), and the stroke volume in the AP group also tended to be lower (P=.057) and their arteriovenous oxygen difference was significantly greater (P<.01). Although minute ventilation per unit of carbon dioxide production was similar in the Fontan groups at this level of exercise, children in the TCPC group breathed faster by approximately 10 breaths per minute (P<.005). Conclusions: At submaximal exercise, children who had undergone the TCPC Fontan procedure had pulmonary hemodynamics superior to those of children who had undergone the AP procedure, largely because of respiratory adaptation that permitted blood to be 'sucked' into the lungs. To achieve the same maximal exercise performance, children who had undergone the AP procedure had a superior metabolic adaptation to exercise stress.
Keywords: adolescent; article; cardiopulmonary hemodynamics; child; clinical article; controlled study; exercise; female; Fontan procedure; heart stroke volume; human; lung blood flow; lung hemodynamics; lung minute volume; male; oxygen consumption; preschool child; priority journal; school child; surgical technique

Treatment options for hypoplastic left heart syndrome: a mother's perspective. - Swanson, L.T. (Critical care nurse, 1995)
The congenital heart defect of HLHS is nearly uniformly fatal without intervention. As surgeons gain experience with the techniques the success rates are improving; more infants with HLHS are being offered hope for survival and quality of life. The critical nature of this diagnosis, the relatively new treatment options, and uncertainty of the surgical outcome impose tremendous stress on the parents. Choice of treatment is difficult and should be made in collaboration with the attending physician. Although the first year of my son's life was difficult, the past 5 years have been wonderful. He continues to thrive and enjoy most of the activities other 6-year-olds enjoy. In retrospect, palliative surgery was a good option for him. As both his mother and a cardiac nurse, I recognize that he may once again require surgical intervention, but I am encouraged that medical and surgical advances are being made for children with HLHS.
Keywords: article; case report; decision making; human; hypoplastic left heart syndrome; male; mother; newborn; palliative therapy; psychological aspect

Hypoplastic left heart syndrome: Anesthetic care prior to transplantation or surgical palliation - Testa, L.; Tobias, J.D.; Kavanaugh-McHugh, A. (Journal of Clinical Anesthesia, 1994)
Hypoplastic left heart syndrome is the most common lethal cardiac defect in neonates. Options for treatment include cardiac transplantation and surgical palliation. When cardiac transplantation is chosen as the preferred option, a considerable delay may occur until a suitable donor is available. During this time, anesthetic care may be required for various surgical procedures. Associated anomalies seen in these infants and the anesthetic implications imposed by the abnormal cardiac anatomy are discussed.
Keywords: atropine; etomidate; fentanyl; prostaglandin E1; acrocephalosyndactyly; anesthetic recovery; article; artificial ventilation; case report; congenital heart malformation; Ellis van Creveld syndrome; female; heart transplantation; human; human cell; human tissue; hypoplastic left heart syndrome; infant; Noonan syndrome; palliative therapy; priority journal; syndrome CHARGE

Prediction of quality of life at long-term follow-up after Fontan operation by scoring risk factors - Park, I.; Nakazawa, M.; Imai, Y.; Sawatari, K.; Momma, K. (Japanese Circulation Journal, 1994)
Many factors will determine the quality of life at long-term follow-up after the Fontan operation. We tried to predict the long-term outcome of modified Fontan operation based on the combined assessment of various preoperative data. The preoperative condition was evaluated by a scoring system in which multilevel scores (from zero to 8 points) were given to a total of 14 morphological and physiological factors according to the contribution of each factor to mortality. The major factors were the association of the extracardiac total anomalous pulmonary venous connection, pulmonary arterial vascular resistance, mean pulmonary arterial pressure, PA index, ejection fraction of the main ventricle, and creatinine clearance. Points for each factor were determined according to surgical mortality, with zero points indicating no increased risk. The total score, i.e., the sum of the points for each item, in each patient was analyzed in relation to the patient's quality of life over a long-term follow-up, as evaluated by questionnaires. Twenty-six of 29 patients with scores of 5 or less showed normal or almost normal life long after the operation, whereas 5 of 10 with higher scores had restricted physical and daily activity. In conclusion, good preoperative condition predicts a good quality of life long after the Fontan operation. In addition, the concept of taking into account all possible risk factors as a comprehensive indicator may be useful in predicting long-term results.
Keywords: adolescent; adult; article; child; clinical article; clinical trial; follow up; Fontan procedure; great vessels transposition; heart atrium septum defect; heart right ventricle double outlet; heart single ventricle; human; hypoplastic left heart syndrome; quality of life; tricuspid valve atresia

Recurrence risk for major congenital heart defects in Sweden: A registry study - Pradat, P. (Genetic Epidemiology, 1994)
During the period 1981-1986, 1605 infants presenting a major congenital heart defect (CHD) were identified in Sweden. Using the personal identification numbers of the mothers, 1507 of them could be linked to the Medical Birth Registry and two controls were selected for each infant. For this total of 4521 infants, 2686 postoccurrence sibs born during the period 1981-1989 were identified from the Medical Birth Registry. The tendency to have one or more sibs was higher among cases than among controls and was correlated to the life status of the proband. This tendency did not vary according to the type of CHD when controlling for life status. The prevalence at birth of CHD was almost four times higher among sibs of CHD infants than among sibs of normal infants. The tendency to have a sib with an extracardiac malformation did not differ between CHD probands and normal probands. The importance of only including births occurring after the proband when evaluating recurrence risks is stressed.
Keywords: aortic coarctation; artery malformation; article; congenital heart malformation; controlled study; endocardial cushion defect; female; heart septum defect; human; hypoplastic left heart syndrome; infant; major clinical study; male; mitral valve disease; recurrence risk; register; sibling; Sweden; tricuspid valve disease

Congenital heart diseases in Bohemia. Epidemiologic data - Samanek, M. (Cor et Vasa, 1994)
The prevalence rate of cardiac malformations (CM) in Bohemia is 6.64/1000 live births and 21/1000 stillbirths. The most common were ventricular and atrial septal defects, pulmonary and aortic stenoses in live-born infants, and ventricular septal defect, hypoplastic left heart syndrome and transposition in stillborns. Seasonal and regional differences of the prevalence were found in the whole cohort and in individual forms of CM. The boys to girls ratio was 1.09:1 in live births and 1.3:1 stillbirths. Boys predominated in double outlet right ventricle, transposition and aortic stenosis and girls in patent ductus arteriosus, Ebstein's anomaly and truncus arteriosus. 35.3% of all CM, i.e., 2.36/1000 of all live births presented with life-threatening symptomatology or died. Of all children born with CM, 78.3% reached the age of 10. The 10-year survival rate was highest in pulmonary stenosis, atrial septal defect, aortic stenosis, ventricular septal defect and patent ductus arteriosus and lowest in hypoplastic left heart, truncus arteriosus and pulmonary atresia. Only 17.7% of suviving children are on medication. Physical activity is normal in 65.4%, slightly reduced in 28.4%, and reduced in 5.9% of long-term survivors.
Keywords: article; child; congenital heart disease; human; infant; major clinical study; newborn; quality of life

Infant heart transplantation: A survey of physician beliefs - Higgins, S.S.; Paul, S.M.; Hardy, C.E.; Ternullo-Retta, C.; Affonso, D. (Journal of Heart and Lung Transplantation, 1994)
Heart transplantation in infancy has become the fastest growing area in pediatric heart transplantation. Infant heart transplantation presents a profoundly complex decision-making situation for parents. There is a relationship between physician beliefs and their manner of presenting heart transplantation options to parents. The purpose of this study was (1) to determine the beliefs of physicians about neonatal heart transplantation, (2) to define their perceptions about their role in counseling parents about heart transplantation, and (3) to evaluate the differences of beliefs by physician specialties (pediatric cardiologists, noenatologists, and pediatricians) and practice settings (university, private, health maintenance organization). A questionnaire was designed to survey 117 physicians on their beliefs about heart transplantation. Findings revealed significant differences related to beliefs: (1) infant heart transplantation is still experimental (pediatric cardiologists, 56%; neonatologists, 85%; pediatricians, 63%; p < 0.05), (2) neonatal heart transplantation is acceptable for fatal heart disease (pediatric cardiologists, 86%; neonatologists, 73%; pediatricians, 63%; p < 0.05), (3) newborn heart transplantation should be presented negatively to protect parents from potential negative consequences on their quality of life (pediatric cardiologists, 14%; neonatologists, 33%; pediatricians, 48%; p < 0.05); (university, 25%; private, 18%; health maintenance organization, 61%; p < 0.05), and (4) infants with hypoplastic left heart syndrome should not be treated (university, 28%; private, 23%; health maintenance organization, 55%; p < 0.05). Though it is critical to impart information to parents with a fair representation of infant heart transplantation, we conclude that many physicians surveyed had a knowledge deficit or bias about the current state of the art of infant heart transplantation.
Keywords: article; fatality; heart disease; heart transplantation; human; medical decision making; medical practice; newborn surgery; physician attitude; priority journal

Systolic and diastolic function in tricuspid valve atresia before the Fontan operation - Sandor, G.G.S.; Patterson, M.W.H.; LeBlanc, J.G. (American Journal of Cardiology, 1994)
Systolic and diastolic function were assessed at preoperative cardiac catheterization in 6 patients with classic tricuspid atresia and were compared with those in control subjects. All patients had systemic-to- pulmonary shunts. Left ventricular end-systolic and end-diastolic volumes and masses were significantly larger in the patient group; stroke volume and the ratio of volume to mass were also higher, but not significantly. Mean end- diastolic, peak systolic and end-systolic pressures were similar. Mean stress at end-systole and peak systole were significantly higher in the patient group. Operant chamber stiffness tended to be lower than normal, but was not statistically significant, and myocardial stiffness was normal for the patient group also. Indexes of systolic function were compared. The rate- corrected mean velocity of fiber shortening in the patient group was lower and its relation with stress at end-systole was variable with 4 abnormal patients. The ratio of stress at end-systole/end-systolic volume was significantly lower in patients. The duration of hospital stay did not correlate with end-diastolic volume or any parameter. Thus, this study found abnormalities of load-dependent and independent indexes of systolic function with normal diastolic function in young preoperative patients with tricuspid atresia.
Keywords: article; child; clinical article; controlled study; Fontan procedure; heart catheterization; heart ejection fraction; heart function; heart left ventricle enddiastolic volume; heart left ventricle volume; heart stroke volume; hospitalization; human; preschool child; priority journal; tricuspid valve atresia

Infant heart transplantation: a survey of physician beliefs. - Higgins, S.S.; Paul, S.M.; Hardy, C.E.; Ternullo-Retta, C.; Affonso, D. (The Journal of heart and lung transplantation : the official publication of the International Society for Heart Transplantation, 1994)
Heart transplantation in infancy has become the fastest growing area in pediatric heart transplantation. Infant heart transplantation presents a profoundly complex decision-making situation for parents. There is a relationship between physician beliefs and their manner of presenting heart transplantation options to parents. The purpose of this study was (1) to determine the beliefs of physicians about neonatal heart transplantation, (2) to define their perceptions about their role in counseling parents about heart transplantation, and (3) to evaluate the differences of beliefs by physician specialties (pediatric cardiologists, neonatologists, and pediatricians) and practice settings (university, private, health maintenance organization). A questionnaire was designed to survey 117 physicians on their beliefs about heart transplantation. Findings revealed significant differences related to beliefs: (1) infant heart transplantation is still experimental (pediatric cardiologists, 56%; neonatologists, 85%; pediatricians, 63%; p < 0.05), (2) neonatal heart transplantation is acceptable for fatal heart disease (pediatric cardiologists, 86%; neonatologists, 73%; pediatricians, 63%; p < 0.05), (3) newborn heart transplantation should be presented negatively to protect parents from potential negative consequences on their quality of life (pediatric cardiologists, 14%; neonatologists, 33%; pediatricians, 48%; p < 0.05); (university, 25%; private, 18%; health maintenance organization, 61%; p < 0.05), and (4) infants with hypoplastic left heart syndrome should not be treated (university, 28%; private, 23%; health maintenance organization, 55%; p < 0.05). Though it is critical to impart information to parents with a fair representation of infant heart transplantation, we conclude that many physicians surveyed had a knowledge deficit or bias about the current state of the art of infant heart transplantation.
Keywords: article; cardiology; congenital heart malformation; counseling; female; health maintenance organization; health personnel attitude; heart transplantation; human; human relation; male; middle aged; neonatology; newborn; parent; patient attitude; patient participation; pediatrics; physician; private practice; university hospital

Midline cerebral dysgenesis, dysfunction of the hypothalamic-pituitary axis, and fetal alcohol effects - Coulter, C.L.; Leech, R.W.; Schaefer, G.B.; Scheithauer, B.W.; Brumback, R.A. (Archives of Neurology, 1993)
Objective. - Neuropathologic evaluation was performed on an infant with fetal alcohol effects. Design. - Coronal brain sections and representative tissue blocks stained with hematoxylin-eosin, silver stain, and immunocytochemical stains for hypothalamic and pituitary hormones were evaluated for neuropathologic abnormalities. Patient. - A 2.5-month-old American Indian girl who had been exposed to first-trimester maternal binge alcohol abuse died after persistent problems of growth failure, sodium imbalance, aberrant temperature regulation, respiratory distress, and seizures. Results. - Autopsy revealed severe microcephaly, hypertelorism, midfacial hypoplasia, a high-arched palate, shortened palpebral fissures, and a small brain. The frontal lobes were fused anteriorly; olfactory bulbs and tracts were absent; and optic nerves were hypoplastic. An enlarged and bulbous hypothalamus obscured the pituitary gland. The thalamus and caudate nuclei were fused across the midline. Posteriorly, the single ventricle split to form rudimentary lateral horns. The anterior corpus callosum, septum pellucidum, fimbria, and fornices could not be identified. The anterior commissure and supraoptic nuclei were microscopically present. Many Purkinje cells were horizontally positioned, with abnormal dendritic structure. The posterior pituitary lobe was absent, and the infundibulum was flanked by a hypoplastic adenohypophysis and a large subarachnoid heterotopia. Immunocytochemical studies identified only vasopressin and neurophysin in the hypothalamus and only growth hormone and prolactin in the pituitary gland. Conclusion. - To our knowledge, an association between fetal alcohol effects and a complex cerebral anomaly with features of incomplete holoprosencephaly and septo-optic dysplasia has not previously been reported and suggests a possible common pathogenesis needing further study.
Keywords: article; brain malformation; case report; clinical feature; endocrine disease; female; fetal alcohol syndrome; high arched palate; holoprosencephaly; human; hypertelorism; hypothalamus hypophysis system; infant; microcephaly; optic nerve disease; priority journal; syndrome

Pediatric cardioplegic techniques. - Drinkwater, D.C.; Laks, H. (Seminars in thoracic and cardiovascular surgery, 1993)
We use warm induction and reperfusion with amino acid enhancement on all neonates and preoperatively stressed patients to induce arrest without contracture and to replete high-energy substrates. Blood cardioplegia is used in all age groups. We then employ hypothermia in the majority of patients (all neonates), ranging from deep (18 degrees C), to moderate (26 degrees to 28 degrees C), with warm or near normothermia used in only simpler anatomic repairs. The clear benefits of hypothermia in conferring additional cardiac and systemic ischemic protection along with the relatively greater ease of cooling and rewarming in the pediatric patient warrant its continued use in the majority of open-heart cases. Calcium levels are maintained in the 0.3 to 0.5 mM/L range during the conduct of the operation and reperfusion phase. Before removal from bypass, calcium is administered through either bolus or continuous drip technique to provide a normocalcemic level of 1 to 1.2 mM/L. This close attention is particularly important in the neonate to avoid contracture injuries and to maximize cardiac function, and is warranted if citrate-phosphate-dextrose (CPD)-containing transfusion or prime components are used. Preoperative evaluation for aortopulmonary collaterals with coil embolization is routinely performed, and is particularly important in single ventricle physiology where preserved myocardial function is so vital to a favorable outcome. The opportunity to perform some surgeries off bypass, such as on the RV outflow tract, may be used whenever it represents a viable alternative in very young or ill patients. Similarly, the majority of Glenn shunts, for example, are performed using a caval-RA shunt without formal cardiopulmonary bypass.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: article; cardiopulmonary bypass; child; congenital heart malformation; heart arrest; heart muscle reperfusion; human; methodology; pathophysiology

Bless the babies: One hundred fifteen late survivors of heart transplantation during the first year of life - Bailey, L.L.; Gundry, S.R.; Razzouk, A.J.; Wang, N.; Sciolaro, C.M.; Chiavarelli, M.; Branson, B.; Zorn, E.; Eby, W.; Allard, M.; Applegate, R.; Brauer, S.; et al. (Journal of Thoracic and Cardiovascular Surgery, 1993)
There is a rapid growth of interest in heart transplantation therapy during early infancy. From 10% to 25% of the infants who are listed for transplantation annually have died while awaiting a donor heart. There has been no significant trend in this variable. Since November 1985, 140 consecutive orthotopic transplantation procedures were performed in 139 infants who were from 3 hours to 12 months of age. Indications for transplantation included hypoplastic left heart syndrome (63%), other complex structural anomalies (29%), myopathy (6.5%), and tumors (1.5%). Most recipients had ductus-dependent circulation and received continuous infusion of prostaglandin E1. Heart donors were usually victims of trauma, sudden infant death, or birth asphyxia. A donor-recipient weight ratio of 4.0 or less was found to be acceptable. The amount of time the graft underwent cold ischemia, ranged from 64 to 576 minutes. The procurement process was facilitated by a single dose of cold crystalloid cardioplegic solution and cold immersion transport. Profound hypothermic circulatory arrest was used for graft implantation. One hundred twenty-four (89%) recipients survived transplantation and were discharged from the hospital. There were 9 late deaths, which resulted in an 83% overall survival. The 5-year actuarial survival is 80%. The survival among newborn recipients (n = 60) at 5 years is 84%. Chronic immunomodulation was cyclosporine-based and steroid-free. Surveillance was noninvasive and relied heavily on echocardiography, electrocardiography, and clinical intuition. There was one documented late lethal infection, tumor was not encountered, and coronary occlusive disease was known to exist in only one long-term survivor. We concluded that transplantation results in excellent life quality and is a highly effective and durable therapy when applied during early infancy.
Keywords: cyclosporine; prostaglandin E1; article; graft rejection; heart transplantation; human; hypoplastic left heart syndrome; infant; major clinical study; newborn; organ donor; pediatric surgery; priority journal; quality of life; survival time

Natural history and patterns of recovery of contractile function in single left ventricle after Fontan operation - Sluysmans, T.; Sanders, S.P.; Van der Velde, M.; Matitiau, A.; Parness, I.A.; Spevak, P.J.; Mayer Jr., J.E.; Colan, S.D. (Circulation, 1992)
Background. Before the era of the Fontan procedure, the typical course of patients with single left ventricle (LV) consisted of heart failure and death during the second or third decade of life. Despite the advent of effective palliative therapy, ventricular dysfunction remains a significant clinical problem for these patients. Methods and Results. To investigate the causes of ventricular dysfunction in these patients and to determine whether Fontan- type repair reverses deterioration of LV function, the ventricular dimensions, volume, shape, wall stress, and systolic function were determined by echocardiography in 84 patients 0.2-35 years old with double-inlet single LV or tricuspid atresia. Measurements were obtained in 67 patients after palliation (arterial shunt or pulmonary artery band) and in 47 patients a median of 4.4 years after a Glenn (n=9) or a Fontan operation (n=38). Before a Fontan procedure, ventricular volumes were 2 to 3 times normal. Ventricular afterload, assessed as circumferential and meridional end-systolic wall stress, became abnormal after 2 years of age. With age, LV shape changed progressively from ellipsoidal to spherical, as indicated by the decrease in long axis:short axis ratio from normal (1.9) toward unity. Concomitantly, the ratio of circumferential to meridional end-systolic wall stress fell from 1.3 to unity, the ratio of a sphere at equilibrium. This age-related change in shape and load occurred in concert with progressive deterioration of LV systolic function and contractility. Aortic oxygen saturation, an indicator of pulmonary blood flow and therefore volume work in single-ventricle physiology, was inversely and independently correlated with contractility. In the group of patients in whom a Glenn or a Fontan operation was performed at <10 years of age, ventricular dimensions, volumes, and wall stress diminished and LV function and contractility improved after surgery (p<0.001). In patients undergoing surgery after 10 years of age, few had improvement of LV function after surgery. Postoperative ventricular function and contractility were inversely related to age at surgery and to aortic oxygen saturation measured before surgery. Conclusions. Although Fontan-type repair of single ventricle early in life is associated with reversal of the abnormal contractile mechanics associated with age and volume load, this capacity for recovery diminishes with age at surgery.
Keywords: adolescent; adult; arterial oxygen saturation; article; child; echocardiography; Fontan procedure; heart left ventricle contractility; heart left ventricle function; heart left ventricle volume; heart single ventricle; hemodynamic parameters; human; infant; major clinical study; onset age; palliative therapy; priority journal; prognosis; tricuspid valve atresia

Ventricular performance before and after fontan repair for univentricular atrioventricular connection: Angiographic and radionuclide assessment - Akagi, T.; Benson, L.N.; Green, M.; Ash, J.; Gilday, D.L.; Williams, W.G.; Freedom, R.M. (Journal of the American College of Cardiology, 1992)
Objectives. This study was designed to evaluate changes in ventricular volume, mass and cardiac function before and after creation of an atrial to pulmonary connection in patients with a univentricular atrioventricular connection. Background. Intact systolic and diastolic performance is critical for successful establishment of an atrial dependent circulation, and few studies are available comparing cardiac performance before and after creation. Methods. With the use of radionuclide blood pool imaging and ventricular cineangiography, 54 patients (mean age 6.4 ± 3.4 years) were studied. Twenty-eight patients were investigated preoperatively and 36 > 1 year after repair and compared with a control population. Results. Before operation, end-diastolic volume and wall mass were significantly increased compared with those of control subjects; however, the mass/volume ratio was normal (1.08 ± 0.31 g/mol for the preoperative group; 0.97 ± 0.19 for control subjects). Although end-diastolic volume returned to normal after the procedure, wall mass remained elevated and contributed to an elevated mass/volume ratio (1.20 ± 0.38 g/ml). After the procedure, systemic vascular resistance index was significantly elevated compared with that before surgery or with that of control subjects (1,199 ± 373, 2,120 ± 645, 1,556 ± 275 dynes · s · cm-5 · m2: pre- and postrepair and control subjects, respectively). Radionuclide studies demonstrated that preoperative ejection fraction (52 ± 9, 50 ± 9, 60 ± 8%), peak ejection (2.58 ± 0.66, 2.95 ± 0.81, 3.73 ± 0.70 EDV/s) and peak filling rates (2.84 ± 0.75, 2.75 ± 0.79, 3.84 ± 0.51 end-diastolic volumes [EDV/s]) were significantly reduced compared with those of control subjects and remained so after surgery. Conclusions. These data suggest that systolic and diastolic function is depressed preoperatively in these patients, remains unchanged after the creation of an atrial-dependent circulation and is associated with an increased systemic vascular resistance. Long-term issues addressing preservation of cardiac function need to be prospectively studied.
Keywords: article; atrioventricular conduction; controlled study; diastole; Fontan procedure; heart left ventricle mass; heart left ventricle performance; human; infant; major clinical study; priority journal; scintiangiography; systole

Bidirectional cavopulmonary anastomosis in congenital heart disease. Functional and clinical outcome - Giannico, S.; Santoro, G.; Marino, B.; Cicini, M.P.; Marcelletti, C. (Herz, 1992)
The bidirectional cavopulmonary anastomosis is a surgical procedure suitable for patients with cyanotic congenital heart disease and univentricular physiology. This operation is able to increase the effective pulmonary blood flow without any additional load on the cardiac work and without any further distortion on the pulmonary artery branches. The cavopulmonary anastomosis can represent the first stage for patients destined for Fontan repair or a definitive palliative operation in high risk Fontan candidates. In order to test the hypothesis of a definitive palliation by cavopulmonary anastomosis in this kind of patients, we evaluated the hemodynamic data before and after this surgical approach and compared these data with their clinical and functional outcome. We evaluated 74 patients submitted to bidirectional cavopulmonary anastomosis by either hemodynamic or functional evaluation. End-diastolic and end-systolic ventricular volumes were significantly reduced by bidirectional cavopulmonary anastomosis (p < 0.0005). Despite these data and a normal ambulatory ECG, spirometry and echocardiographic analysis, the stress test showed discouraging results. In fact, mean work time and peak heart rate were significantly different from normal values showing an impaired functional capacity of these children. In conclusion we think that bidirectional cavopulmonary anastomosis can not be considered an adequate definitive palliation but it represents a very good stage to preserve the pulmonary arteries and to prepare the systemic ventricle towards the Fontan repair.
Keywords: adolescent; adult; anastomosis; article; child; congenital heart disease; cyanotic heart disease; female; heart left ventricle enddiastolic volume; human; infant; major clinical study; male

Hypoplastic left heart syndrome: access to medical care. - Huhta, J. (Journal of perinatology : official journal of the California Perinatal Association, 1992)
Keywords: article; congenital heart malformation; congenital malformation; decision making; health care delivery; heart ventricle; human; newborn; prenatal care; syndrome; treatment refusal

Case study: infant transplantation: a change of heart. - Feliciano, S.M.; Girard, N.J.; Calhoon, J.H. (Seminars in perioperative nursing, 1992)
The majority of infant heart transplants are for the correction of hypoplastic left heart syndrome (HLHS). This article will describe the preoperative, intraoperative, and postoperative care for perioperative and pediatric intensive care areas implemented for HLHS infant heart transplantation at Medical Center Hospital, San Antonio, TX. The surgical procedure is given. Dimensions of psychosocial care and education of the parents are briefly described.
Keywords: article; heart surgery; human; infant; methodology; newborn; newborn nursing; nursing; operating room personnel; patient care planning

Intermediate term results of infant orthotopic cardiac transplantation from two centers - Backer, C.L.; Zales, V.R.; Harrison, H.L.; Idriss, F.S.; Benson Jr., D.W.; Mavroudis, C. (Journal of Thoracic and Cardiovascular Surgery, 1991)
Orthotopic cardiac transplantation has become established for selected infants with severe forms of congenital heart disease. This study reviews the combined experience and intermediate term results of infants undergoing orthotopic cardiac transplantation from Children's Memorial Hospital, Chicago, and Kosair Children's Hospital, Louisville. From June 1986 through December 1989, 20 orthotopic cardiac transplantations were performed in 19 patients. Sixteen patients had variants of hypoplastic left heart syndrome. One infant had anomalous origin of the left coronary artery with severe ischemic cardiomyopathy. Two infants had aortic stenosis with endocardial fibroelastosis, and one had extracorporeal membrane oxygenation as a bridge to transplantation. Immunosuppression included cyclosporine, azathioprine (Imuran), and corticosteroids with an effort to wean the patients from steroids by 6 months to 2 years. Three early deaths resulted - from technical errors in two patients and from hyperacute rejection in one patient at 3 days. Four late deaths have occurred. Two patients died at 2 and 13 months of acute rejection. One patient died at 15 months of acute rejection after retransplantation. One patient died at 7 months of respiratory syncytial viral pneumonia. The remaining 12 patients are surviving 5 to 47 months (mean 20 months) after orthotopic cardiac transplantation. Rejection surveillance in the first 6 months is by clinical signs supplemented by echocardiography, electrocardiography, and cell cycle analysis; endomyocardial biopsy is used after 6 months of age. For the cumulative series, 24 episodes of suspected rejection have been treated during 277 at-risk patient months with intravenous methylprednisolone (Solu-Medrol) (n = 18) and monoclonal antibody (OKT3) (n = 6), for an incidence of 1.04 episodes of rejection per patient per year. Serious posttransplantation infections including endocarditis, catheter sepsis, meningitis, and colonic perforation were successfully treated in four patients. Subjectively, their quality of life is excellent as shown by normal growth and development milestones and a low hospital readmission rate (1.4 episodes per patient per year). These encouraging intermediate term results warrant continued application of infant orthotopic cardiac transplantation for severe forms of congenital heart disease.
Keywords: article; clinical article; congenital heart disease; graft rejection; heart transplantation; human; infant; mortality; priority journal

Impact of Fontan operation on left ventricular size and contractility in tricuspid atresia - Gewillig, M.H.; Lundstrom, U.R.; Deanfield, J.E.; Bull, C.; Franklin, R.C.; Graham Jr., T.P.; Wyse, R.K. (Circulation, 1990)
Left ventricular dimensions and contractility were determined by echocardiography in 33 patients with tricuspid atresia in 1985 and again in 1988. Eight patients remained palliated throughout the 3-year period; neither the left ventricular end-diastolic diameter (153 ± 15% of normal vs. 157 ± 19%, p = NS) nor a load-independent index of contractility (rate-corrected velocity of shortening [VCFc]/end-systolic meridional stress [ESSM]) changed. Eleven patients underwent a Fontan operation during the study and were reevaluated at least 6 months after surgery; left ventricular dimension decreased (130 ± 15% vs. 114 ± 19%, p < 0.001), and the contractility index VCFc/ESSM improved (p < 0.05). Fourteen patients had undergone a Fontan operation 0.9-9.5 years (mean, 4.2 years) before initial examination in 1985. Over the 3-year period, left ventricular dimensions did not change (121 ± 17% vs. 118 ± 11%, p = NS), but the contractility index showed significant improvement (p < 0.01). Eight additional patients were studied just before and after a Fontan operation to examine the early effects of surgery. Left ventricular dimensions decreased from 130 ± 14% to 100 ± 13% by 10 days p < 0.001) with no further change at 2 months. An inappropriate degree of ventricular hypertrophy was observed in only the early postoperative period. Successful Fontan repair resutls in rapid reduction of left ventricular size, followed by regression of hypertrophy to a normal mass-to-volume ratio. Operating at more favorable dimensions and loading conditions results in an early increase in left ventricular contractility, which further improves in the medium term follow-up.
Keywords: adolescent; article; child; clinical article; diagnosis; echocardiography; female; heart left ventricle performance; human; male; priority journal; renard fontaine syndrome; school child; tricuspid valve atresia

Palliative Mustard operation: an expanded horizon. - Corno, A.F.; Parisi, F.; Marino, B.; Ballerini, L.; Marcelletti, C. (European journal of cardio-thoracic surgery : official journal of the European Association for Cardio-thoracic Surgery, 1987)
From March 1982 to December 1983, five patients with a mean age 7 years (4 months-16 years) underwent a palliative Mustard operation for complex cardiac anomalies. The diagnoses were: univentricular heart with pulmonary vascular obstructive disease (PVOD) (2 cases); criss-cross heart with intact atrial septum, ventricular septal defect (VSD), transposition of the great arteries (TGA) and moderate pulmonary stenosis; isolated atrioventricular discordance with VSD; TGA, diminutive right ventricle and multiple VSDs. Cardiac catheterization showed unfavourable direction of flow: the oxygen saturation in the aorta was lower than in pulmonary artery, with a mean difference of 13.5% (range 6% to 30%). In no case was anatomical or physiological repair considered advisable because of the unfavourable intracardiac anatomy or the presence of PVOD. In two patients the atrial rerouting was accompanied by pulmonary artery banding. There were no hospital or late deaths in a mean follow-up of 36 months (range 29 to 50 months). The mean post-operative arterial oxygen saturation was 95.4% (range 92% to 99%).
Keywords: adolescent; article; congenital heart malformation; evaluation study; female; follow up; human; infant; male; mortality; palliative therapy; quality of life; procedures; treatment outcome

Analysis of the effects of Blalock-Taussig shunt on ventricular function and the prognosis in patients with single ventricle - Kuroda, O.; Sano, T.; Matsuda, H. (Circulation, 1987)
Twenty-four patients with single ventricle, six with single left (SLV) and 18 with single right (SRV) ventricle, who received a Blalock-Taussig (BT) shunt at an average age of 3.2 years were studied. Ventricular function was assessed angiographically by end-diastolic volume index (EDVI) and ejection fraction (EF), and attempts were made to measure ventricular mass index (VMI) and VM/EDV. In 14 patients, the preoperative and postoperative results (average 2.4 years after placement of BT shunt) were compared in SLV (n = 5) and SRV (n = 9) groups. The SLV group showed significant increases in EDVI, VMI, and VM/EDV without a significant change in EF. The SRV group showed significant increases in EDVI and VMI, while EF decreased and VM/EDV was unchanged. Late death from congestive heart failure occurred in five patients with SRV. Three patients with atrioventricular valve regurgitation suffered late death. Among the patients with SRV, the late death group had significantly lower preoperative EF and VM/EDV compared with the survivors (n = 13). All of those with a preoperative EF of less than 0.50 and a VM/EDV of less than 0.35 g/ml suffered late death. In summary, patients with SRV appear to fail to develop adaptational hypertrophy to volume loading after the BT shunt procedure, with concomitant depression in ventricular pump function. Also, late cardiac failure seems likely to develop when low EF and VM/EDV are present preoperatively.
Keywords: Blalock Taussig shunt; child; clinical article; congenital disorder; great blood vessel; heart; heart single ventricle; heart ventricle function; human; priority journal; therapy; ventriculography

Hypoplastic left heart syndrome: options for the infant and the family. - Hedenkamp, E.A. (Progress in cardiovascular nursing, 1987)
Keywords: article; congenital heart malformation; congenital malformation; heart; heart ventricle; hemodynamics; human; human relation; newborn; nursing; pathophysiology; syndrome

The hypoplastic left heart syndrome: Evidence of preoperative myocardial and hepatic infarction in spite of prostaglandin therapy - Moodie, D.S.; Gill, C.C.; Sterba, R. (Annals of Thoracic Surgery, 1986)
From February, 1983, to November, 1984, 11 infants with hypoplastic left heart syndrome were managed medically prior to operative intervention. Only 2 of the 11 infants appeared to be in mild distress at birth. Despite relatively normal Apgar scores, 9 of the infants were seen in shock. All patients were managed medically with fluid restriction, diuretics, and the institution of prostaglandin E1. There was marked improvement in arterial pH from a mean value of 7.13 prior to prostaglandin to 7.42 following prostaglandin infusion. There was also a dramatic decrease in the serum creatinine level from a mean pretreatment level of 1.5 mg/dl to 0.7 mg/dl following infusion. Ten of the 11 infants were operated on at a mean age of 4 days with a Norwood or conduit procedure. Three infants who died at 3, 13, and 24 days of age had sustained myocardial infarctions prior to operation. Three patients also had multiple infarcts of the liver. Three patients are alive 23, 22, and 6 months after operation, and are growing and developing normally. The ability to maintain the infant with hypoplastic left heart syndrome in a stable hemodynamic condition has made surgical palliation a realistic option for this otherwise fatal anomaly. Nevertheless, preoperative infarctions of the heart and viscera continue to play a major role in mortality.
Keywords: creatinine; prostaglandin; prostaglandin E1; arterial pH; autopsy; blood and hemopoietic system; clinical article; drug dose; drug efficacy; drug therapy; heart; heart infarction; histology; human; hypoplastic left heart syndrome; infant; intravenous drug administration; liver; liver infarction; newborn; priority journal; serum; surgery; therapy

Left ventricular wall stress and contractile function in childhood: Normal values and comparison of Fontan repair versus palliation only in patients with tricuspid atresia - Graham Jr., T.P.; Franklin, R.C.G.; Wyse, R.K.H. (Circulation, 1986)
Left ventricular wall stress and contractile function were determined by echocardiographic methods in 23 patients with tricuspid atresia after palliation only (group 1), in 19 patients after Fontan repair (group 2), and in 24 age-matched normal subjects. End-diastolic dimension was increased above normal in both groups with tricuspid atresia (group 1 [mean ± SEM] 141 ± 4%, group 2 129 ± 5% of normal; both p < .001) but were not different from each other. Left ventricular end-diastolic volume and wall mass also were increased above normal in both groups (group 1, 126 ± 9 ml/m2 and 194 ± 19 g/m2, respectively, p < .001 and p < .004; group 2, 80 ± 7 ml/m2 and 128 ± 10 g/m2, p < .02 and p < .001), and group 2 patients showed significantly lower values than group 1 patients (p < .001 and p < .004). Meridional end-systolic stress was increased above normal in both groups with tricuspid atresia but was not different between groups (normal, 43 ± 3 g/cm2; group 1, 56 ± 5 g/cm2, p < .02; group 2, 59 ± 7 g/cm2, p < .001). Contractile function estimated by rate-corrected circumferential fiber shortening velocity was abnormal in nine of 23 (39%) group 1 patients and in five of 19 (26%) group 2 patients (percentages not different from each other by nonparametric testing). Contractile function was depressed in one of 11 group 1 patients under 5 years old and in eight of 12 over 5.3 years old. Fontan repair in patients with tricuspid atresia resulted in less volume overload and hypertrophy than palliation only, but an increased afterload and abnormal contractile function persisted in a significant number of patients. Abnormal function is prevalent in patients older than 5 years with palliation only. Prospective data are needed in an attempt to clarify causes of myocardial dysfunction in patients with tricuspid atresia.
Keywords: adult; child; childhood; clinical article; congenital disorder; diagnosis; echocardiography; Fontan procedure; heart; human; palliative therapy; postoperative period; priority journal; therapy; tricuspid valve atresia

Transthoracic intracardiac monitoring lines in pediatric surgical patients: A ten-year experience - Gold, J.P.; Jonas, R.A.; Lang, P. (Annals of Thoracic Surgery, 1986)
A study of 6,690 transthoracic intracardiac monitoring (TIM) catheters in 5,666 pediatrics patients undergoing cardiac surgical procedures during a 10-year period demonstrates the safety of this monitoring method. The utility of TIM catheters in patients undergoing a modified Fontan procedure, those undergoing repair of tetralogy of Fallot, and those with elevated or labile pulmonary resistance is stressed. Right atrial (RA) and left atrial (LA) catheters are particularly safe; they have a low incidence of bleeding complications (RA = 0%, LA = 0.13%) and retention complications (RA = 0.15%, LA = 0.63%). Pulmonary artery (PA) catheters that are introduced through the right ventricular infundibulum have higher complication rates (1.07%); unpredictable hemodynamic compromise occurs in approximately 0.5% of such patients. PA catheters placed through the wall of the atrium have a lower complication rate - approximately equal to that for RA and LA catheters. The benefits of TIM catheters far outweigh the associated risks if care is exercised in placing and removing them, and if complications are rapidly recognized and aggressively managed. The continued use of TIM catheters in pediatric cardiac surgical patients is therefore strongly recommended.
Keywords: case report; child; congenital disorder; congenital heart disease; diagnosis; heart; heart surgery; human; monitoring; pediatrics; priority journal

Causes of death in neonates born with a heart malformation - Samanek, M.; Goetzova, J.; Benesova, D. (International Journal of Cardiology, 1986)
All deceased infants were autopsied in a territory with a population of 1,220,000 inhabitants and a mean of 17,410 live births a year. During a period of 25 years (which preceded the introduction of advanced neonatal cardiac surgery), 393 neonates (6% of all deceased neonates) had died in whom a congenital heart malformation was found at autopsy. 118 (30%) of deaths were due to noncardiac causes. Lethal congenital noncardiac malformations caused death in 38 (10%) neonates. A perinatal disease (including birth trauma) was the cause in 65 (16%) neonates. An association of a noncardiac congenital malformation with a perinatal disease was involved in 6 (2%) neonates and a birth weight lower than 1000 g (together with a lethal perinatal disease or alone) was considered responsible in 9 (2%) neonates. Noncardiac but not unambiguously lethal malformations (mostly multiple) could at least have contributed to the fatal outcome in a further 86 (22%) neonates. A low birth weight could have contributed to death in 102 (26%) neonates, particularly in 42 (11%) neonates with a low birth weight associated with multiple noncardiac nonlethal malformations. A most probable or possible noncardiac cause of death was found in all cases of atrial septal defect, in 93% of tetralogies of Fallot, in 84% of ventricular septal defects, in 72% of hearts with double outlet right ventricle and in 57% of those with aortic coarctation. A congenital heart malformation was considered responsible for a fatal outcome in 82% of cases with discordant ventriculoarterial connexions ('transposition of the great arteries'), 79% of hypoplastic left hearts, 68% of pulmonary atresias and 53% of tricuspid atresias. The high proportion of noncardiac death noted to occur in the first postnatal day was found rapidly to decrease in the following days.
Keywords: autopsy; cause of death; congenital disorder; congenital heart disease; fatality; heart; heart death; human; major clinical study; newborn; priority journal

Hypoplastic left heart syndrome: A review and the report of two cases - Clochesy, J.M.; Whittaker, A.A.; Murdaugh, C.L. (Heart and Lung: Journal of Acute and Critical Care, 1986)
Caring for infants with HLHS and their parents is challenging. Social policies of the 1980s such as 'Baby Doe', 'Baby Fae', and diagnosis-related groups raise additional ethical and economic or financial questions. The nurse must diligently monitor tissue perfusion in the infant and the parents' coping with loss, while struggling with difficult ethical/legal issues.
Keywords: case report; congenital disorder; diagnosis; heart; human; hypoplastic left heart syndrome; newborn; priority journal; survey

Cyanotic congenital heart disease with decreased pulmonary blood flow - Uzark, K. (Nursing Clinics of North America, 1984)
In the past two decades, long-term survival of patients with cyanotic congenital heart disease has dramatically improved. After successful intracardiac repair, many patients can anticipate a normal lifestyle. Health care providers must increase their knowledge of the nature and effects of surgical intervention, the presence, type, and extent of the patient's postoperative residua and sequelae, and the patient's psychosocial adjustment. Prompt surgical intervention and comprehensive follow-up with early identification and treatment of problems will further enhance both survival of patients born with cyanotic heart disease and the quality of life they achieve in the future.
Keywords: child; congenital cyanotic heart malformation; congenital disorder; cyanosis; Ebstein anomaly; Fallot tetralogy; heart; human; lung blood flow; peripheral vascular system; respiratory system; short survey; therapy; tricuspid valve atresia

Radionuclide measurement of left ventricular ejection fraction in tricuspid atresia - Baker, E.J.; Jones, O.D.H.; Joseph, M.C.; Maisey, M.N.; Tynan, M.J. (British Heart Journal, 1984)
In 15 patients with tricuspid atresia and one with tricuspid stenosis the left ventricular ejection fraction was measured by equilibrium gated radionuclide angiography and the results compared with those from a control group of 16 patients. The patients with tricuspid atresia had a significantly depressed ejection fraction. Those who had a surgical shunt or who had had pulmonary artery banding had significantly lower ejection fractions than the remainder. There was no significant correlation between the ejection fraction and age, the arterial oxygen saturation, or the haemoglobin concentration. Five patients were also studied during isometric exercise; three had an abnormal response. Volume overload of the ventricle is identified as one cause of the dysfunction, but other factors may be important. Radionuclide angiography offers a non-invasive method of studying ventricular function in this condition.
Keywords: radioisotope; adult; child; congenital disorder; diagnosis; heart; heart left ventricle ejection fraction; human; major clinical study; priority journal; scintiangiography; tricuspid valve atresia; tricuspid valve stenosis

CT Diagnosis of false aneurysm of the pulmonary artery not demonstrated by angiography: Case report - Shin, M.S.; Ceballos, R.; Bini, R.M.; Ho, K.J. (Journal of Computer Assisted Tomography, 1983)
A 17-year-old patient with tricuspid atresia, palliatively corrected by a right Glenn and a left Potts anastomosis during his early childhood and a banding of the left pulmonary artery 6 years ago, developed a false aneurysm of the left pulmonary artery secondary to the erosion of the band fabric through the vascular wall with subsequent thrombosis, infection, and leakage. The diagnosis was confused by both chest roentgenography and angiography but was accurately made by postcontrast computed tomography (CT). We stress the importance and usefulness of CT in the diagnosis of a false aneurysm, not demonstrated by angiography.
Keywords: adolescent; case report; computer analysis; computer assisted tomography; congenital disorder; diagnosis; false aneurysm; great blood vessel; heart; human; lung artery banding; peripheral vascular system; therapy; tricuspid valve atresia

Side effects of therapy with prostaglandin E1 in infants with critical congenital heart disease - Lewis, A.B.; Freed, M.D.; Heymann, M.A. (Circulation, 1981)
The case reports of 492 infants with critical congenital cardiac disease treated with prostaglandin E1 (PGE1) were reviewed to determine the nature and incidence of intercurrent medical events. 43% of the infants had at least one such event, but only half of these were related to PGE1 and the majority required only minor changes in management. Cardiovascular events were the most common (18% incidence), with cutaneous vasodilation and edema occurring more frequently during intraaortic infusion than during i.v. infusion. Central nervous system events were reported in 16% of the patients. Respiratory depression as reported in 12%, and was particularly common in infants weighing less than 2.0 kg at birth (42%). Hematologic, infectious and renal events appeared for the most part to be unrelated to PGE1. The overall mortality (excluding 19 patients with hypoplastic left-heart syndrome) was 31%; the mortality for the patients with critical coarctation or interruption of the aortic arch was nearly twice that for the cyanotic infants (50% vs 27%). No deaths was attributed to PGE1 administration. During infusion of PGE1, arterial blood pressure and respiratory activity should be monitored carefully and appropriate supportive steps taken if hypotension or respiratory depression occurs. The development of fever or jitteriness may require reduction of the infusion rate and, in view of the possible increased incidence of infections, the prophylactic use of antibiotics is recommended.
Keywords: prostaglandin E1; adverse drug reaction; congenital heart malformation; drug therapy; edema; heart; hypoplastic left heart syndrome; intoxication; intraarterial drug administration; intravenous drug administration; major clinical study; nervous system; neurotoxicity; newborn; patent ductus arteriosus; respiration depression; respiratory system; therapy; vasodilatation

Case histories of neonates with congenital heart disease. - Naganuma, M.; Tsunemoto, M.; Naito, T. (Japanese circulation journal, 1981)
The rate of extracardiac malformation (ECM) associated with congenital heart disease (CHD) is high in neonates. 108 cases of 212 neonates with CHD had ECM (50.9%). Main ECMs were digestive system anomalies (36.1%), chromosomal aberrations (26.8%), respiratory system anomalies (21.3%), CNS anomalies (13.0%), and other (2.7%). Single lesion of left to right shunt accounted for 77.2% (61/79) of CHD with ECM from other than chromosomal aberrations. The prognosis of neonates with CHD without ECM was also studied. Total anomalous pulmonary venous connection, pure pulmonary atresia (PPA), pulmonary stenosis (PS), hypoplastic left heart syndrome are not generally associated with ECM, but the prognosis is poor. Coarctation complex which is sometimes associated with ECM has a poor prognosis in neonates. There is an increase of the survival rate in the patients with hypoxemia, such as PPA or severe PS, extreme tetralogy of Fallot, and tricuspid atresia, which can be managed with prostaglandin E1. PDA associated with respiratory distress syndrome is ideally treated with indomethacin. In recent years, mortality from PDA has decreased in neonates. The mortality rate during the neonatal period was 46.8% (51/109): 37.5% (30/80) died before surgical interventions and 72.4% (21/29) died during or after surgery. Half of neonatal deaths from CHD occurred within 3 days of admission. Thus, early detection, early diagnosis, and early treatment of neonates with CHD is most important.
Keywords: article; central nervous system; chromosome aberration; chromosome disorder; congenital heart malformation; congenital malformation; digestive system malformation; female; human; male; mortality; multiple malformation syndrome; newborn; postoperative complication; prognosis; respiratory tract malformation

Tricuspid atresia with dextroversion: a not very rare combination - Cokkinos, D.V.; Plessas, S.T.; Tolis, G.; Voridis, E.M. (Journal of Thoracic and Cardiovascular Surgery, 1974)
A case of tricuspid atresia with pulmonic stenosis, ventricular septal defect, and normally related great vessels with dextroversion was correctly diagnosed. The patient was treated successfully with a Glenn operation. The association of this complex of congenital defects with dextroversion has not been stressed adequately in the literature. It is emphasized that, in cases of dextroversion with cyanosis, tricuspid atresia should always be suspected.
Keywords: child; congenital heart malformation; cyanosis; dextrocardia; diagnosis; electrocardiography; heart surgery; heart ventricle septum defect; hemoglobin rahere; major clinical study; pulmonary valve stenosis; tricuspid valve; tricuspid valve atresia

Surgical treatment of congenital heart disease during infancy: One and two stage techniques - Cooley, D.A.; Mailman, G.L.; Wukasch, D.C. (J.Cardiovasc.Surg. (Torino), 1972)
Mortality during the first year of life in patients with congenital cardiovascular disease is approximately 60% without surgical treatment. Operation was undertaken in a consecutive series of 1,050 infants in this age group between 1954 and 1970, with survival of 721 Among the anomalies were patent ductus arteriös us, coarctation, aortic stenosis, pulmonary stenosis, aortic vascular ring, total anomalous pulmonary venous return, tricuspid atresia, tetralogy of Fallot, transposition of the great vessels, ventricular septal defect, pulmonary valve atresia and miscellaneous anomalies. Corrective operations were performed when feasible. A palliative operation was chosen for patients with complex anomalies such as transposition of the great vessels, deferring total correction until a more favorable age for open heart surgery was reached. While two staged procedures were used for several anomalies in this series, the authors recently adopted a more aggressive attitude toward total correction during infancy. To achieve open heart conditions they are employing induced hypothermia by surface cooling, temporary venous inflow occlusion and rewarming by partial cardiopulmonary bypass.
Keywords: aggression; aortic stenosis; cardiopulmonary bypass; cardiovascular disease; congenital heart disease; cooling; cryoanesthesia; Fallot tetralogy; great blood vessel; groups by age; hand malformation; heart; heart surgery; heart ventricle septum defect; induced hypothermia; infancy; infant; lung vein drainage anomaly; mortality; occlusion; open heart surgery; patent; patient; pulmonary valve atresia; pulmonary valve stenosis; surgery; survival; tricuspid valve atresia; vascular ring; warming

A rare case of cor triloculare biatriatum - Kositchek, R.J.; Schreiner, B.J. (Angiology, 1971)
The patient, a 'blue baby', had been examined in reveral cardiac centers during his youth, and open heart intervention had been tried without success. The clinical impression at the time of his last hospitalization was tetralogy of Fallot, with secondary polycythemia. On the fifth day he lapsed into coma and died six days later at age 32. At autopsy, a single ventricle with a common atrioventricular valve was demonstrated. There was no rudimentary outlet chamber, but a small muscular band on the left lateral wall was interpreted as a rudimentary ventricular septum. The great arteries were in normal position. Concomitant pulmonary stenosis was of the infundibular type. Since this particular combination of congential anomalies did not appear in the 60 cases analyzed by Van Praagh et al, it would seem to be unique. Congenital cardiac defects, particularly in cyanotic children, are often associated with mental retardation, but this man was a productive free lance writer until his last illness.
Keywords: artery; autopsy; baby; child; coma; erythrocytosis; Fallot tetralogy; general aspects of disease; heart; heart atrioventricular valve; heart single ventricle; interventricular septum; hospitalization; human; juvenile; mental deficiency; patient; pulmonary valve stenosis

The surgical treatment of congenital heart disease with cyanosis - Van Der, H.; Heide, J.N. (Radiol.Clin.Biol., 1970)
The surgical treatment of congenital heart disease with cyanosis is briefly discussed. Among these anomalies the authors include: atrial septal defect associated with valvular pulmonary stenosis; tetralogy of Fallot; complete transposition of the great vessels; total pulmonary vein transposition (total anomalous venous return); tricuspid valve atresia or stenosis; Ebstein's anomaly, and truncus arteriosus peristens. The surgical management of each of these anomalies is discussed, from total correction to temporary or permanent palliation. In this discussion, special emphasis is placed on the common fields which radiologist and surgeon must have in the treatment of these patients. Good teamwork between the cardiologist, the radiologist and the surgeon is an essential condition for the success of these surgical procedures. This holds even more in cases involving emergency operations, such as the making of an atria I septal defect in patients with transpositions of the great vessels or the blind splitting of the pulmonary artery valve in severely cyanotic infants. The emergency operation performed by the surgeon in such cases could not save lives if he were not supported by a cardiologist and radiologist prepared to perform emergency diagnostic procedures at any hour of the day or night.
Keywords: arterial trunk; cardiologist; congenital heart disease; cyanosis; diagnosis; diagnostic procedure; Ebstein anomaly; emergency; emergency surgery; Fallot tetralogy; great blood vessel; heart atrium; heart atrium septum defect; infant; night; palliative therapy; patient; pulmonary artery; pulmonary valve stenosis; pulmonary vein; radiologist; stenosis; surgeon; surgery; surgical technique; teamwork; tricuspid valve atresia; venous return

The surgical treatment of congential heart disease with cyanesis - Van Homan Der Heide, J.N. (Radiol.Clin., 1970)
The surgical treatment of congenital heart disease with cyanosis is briefly discussed. Among these anomalies the authors include: atrial septal defect associated with valvular pulmonary stenosis; tetralogy of Fallot; complete transposition of the great vessels; total pulmonary vein transposition (total anomalous venous 'return); tricuspid valve atresia or stenosis; Ebstein's anomaly, and truncus arteriosus peristens. The surgical management of each of these anomalies is discussed* from total correction to temporary or permanent palliation. In this discussion, special emphasis is placed on the common fields which radiologist and surgeon must have in the treatment of these patients. Good teamwork between the cardiologist, the radiologist and the surgeon is an essential condition for the success of these surgical procedures. This holds even more in cases involving emergency operations, such as the making of an atrial septal defect in patients with transpositions of the great vessels or the blind splitting of the pulmonary artery valve in severely cyanotic infants. The emergency operation performed by the surgeon in such cases could not save lives if he were not supported by a cardiologist and radiologist prepared to perform emergency diagnostic procedures at any hour of the day or night.
Keywords: acid; tritium; arterial trunk; cardiologist; chromosome; congenital heart disease; cyanosis; diagnosis; diagnostic procedure; Ebstein anomaly; emergency; emergency surgery; Fallot tetralogy; great blood vessel; heart atrium septum defect; heart disease; infant; night; palliative therapy; patient; pulmonary artery; pulmonary valve stenosis; pulmonary vein; radiologist; stenosis; surgeon; surgery; surgical technique; teamwork; tricuspid valve atresia; venous return

Transposition of the great arteries with ventricular septal defect. palliation by atrial septostomy and pulmonary artery banding - Waldhausen, J.A. (Circulation, 1969)
Infants with transposed great arteries need atrioseptostomy for adequate intracardiae mixing of the systemic and pulmonic circulations. Those with ventricular septal defect and pulmonary artery hypertension, with or without other associated lesions, usually require further surgical palliation. Postseptostomy measurements of pulmonary artery pressures at systemic levels ' were obtained in ten infants with transposition of the great arteries and ventricular septal defects. Three had. in addition, patent ductus artenosus. and two of these had aortic e-oarelation (one preductal with hypoplasia of the aortic arch). One had transposition of the great arteries, ventricular septal defect, and tricuspid atresia. Four of the patients had surgical septectomy; the remaining seven had balloon atnoseptostomy. All had pulmonary artery banding, the three ductu.s artenosus lesions were ligated; and both coarctations were repaired (one with reconstruction of the aortic arch). The only operative death was in one of the patients with transposition of the great arteries and ventricular septal defect only. When the interatnal communication is adequate in patients with transposition, ventricular septal defect, and pulmonary artery hypertension, pulmonary vascular obstructive changes may be prevented by pulmonary artery banding and surgical correction.
Keywords: trimetazidine; aortic arch; aortic sinus; artery; case report; death; great vessels transposition; heart ventricle septum defect; hypoplasia; infant; interpersonal communication; lung; lung artery; lung artery banding; lung artery pressure; palliative therapy; patent; patient; pulmonary artery aneurysm; pulmonary hypertension; surgery; tricuspid valve atresia

Transposition of the great arteries with ventricular septal defect. palliation by atrial septostomy and pulmonary artery banding - Waldhausen, J.A.; Boruchow, I.; Miller, W.W.; Rashkind, W.J. (Circulation, 1969)
Infants with transposed great arteries need atrioseptostomy for adequate intracardiac mixing of the systemic and pulmonic circulations. Those with ventricular septal defect and pulmonary artery hypertension, with or without other associated lesions, usually require further surgical palliation. Postseptostomy measurements of pulmonary artery pressures at systemic levels were obtained in ten infants with transposition of the great arteries and ventricular septal defects. Three had, in addition, patent ductus arteriosus, and two of these had aortic coarctation (one preductal with hypoplasia of the aortic arch). One had transposition of the great arteries, ventricular septal defect, and tricuspid atresia. Four of the patients had surgical septectomy; the remaining seven had balloon atrioseptostomy. All had pulmonary artery banding; the three ductus arteriosus lesions were ligated; and both coarctations were repaired (one with reconstruction of the aortic arch). The only operative death was in one of the patients with transposition of the great arteries and ventricular septal defect only. When the interatrial communication is adequate in patients with transposition, ventricular septal defect, and pulmonary artery hypertension, pulmonary vascular obstructive changes may be prevented by pulmonary artery banding and surgical correction of the associated lesions.
Keywords: trimetazidine; aortic arch; aortic coarctation; artery; artery ligation; cardiovascular surgery; death; ductus arteriosus; great vessels transposition; heart septum defect; heart ventricle septum defect; hypoplasia; infant; interpersonal communication; intracardiac drug administration; lung artery; lung artery banding; lung artery pressure; palliative therapy; patent ductus arteriosus; patient; pulmonary hypertension; surgery; tricuspid valve atresia

Haemodynamic effects of balloon septostomy in tricuspid atresia - Singh, S.P. (British medical Journal (1857), 1968)
Tricuspid atresia has been regarded as one of the rare congenital cardiac anomalies, but it must be considered in the differential diagnosis of every infant with cyanotic heart disease. The physiological consequences of the anomaly are manifold. Arterial desaturation is caused by complete mixing of systemic venous and pulmonary venous blood in the left atrium. The degree of unsaturation and cardiac handicap depends on the pulmonary flow and the size of the atrial scptal opening. If the atrial sept al defect is small it causes raised right atrial pressure, and this in turn results in raised systemic venous pressure and severe congestive failure. In such cased enlargement of the atrial septal defect should decrease central venous pressure and thus relieve the congestive heart failure. The authors report here the application of the technique of atrial septostomy in a small infant with tricuspid atresia and transposition of the great vessels with an extremely small intra-atrial communication. (18,1,7*).
Keywords: catheter; central venous pressure; congestive heart failure; cyanotic heart disease; differential diagnosis; disability; fatty acid desaturation; great blood vessel; heart atrium septum defect; heart disease; heart left atrium; heart right atrium pressure; hemodynamics; infant; interpersonal communication; tricuspid valve atresia; venous blood; venous pressure

Neonatal cardiac distress. a practical approach to recognition. diagnosis, and management - Cayler, G.G. (California medicine, 1968)
The death rate among neonates with cardiovascular disease is 50% during the first 6 mth. with the majority dying during the first month. With early diagnosis most of these babies could be saved. In approaching the diagnosis of cardiac distress in the newborn, it is important to remember that the types of cardiovascular disease which cause symptoms and death early in life are quite different from those in older children. Lesions such as hypoplasia of the left heart, transposition of the great arteries, endocardial fibroelastosis, pulmonary atresia. mitral atresia, tricuspid atresia and t run cue arteriös us are common, not rare, causes of cardiac distress in the newborn. A classification of neonatal cardiovascular disease! into 7 pathophysiological groups is presented as a basis for an effective,practical approach to the differential diagnosis of the potentially lethal lesions. This approach is simplified further since over 90% of babies with cardiac distress have one of 3 lesions: (1) Large left-to-right shunt (characterized by the presence of massive plethora on the chest roentgenogram), (2) Large right-to-left shunt (association with intense cyanosis) or (3) Severe obstruction (including hypoplasia of the left heart, which is the most common cause of death due to cardiac distress during the first week of life).
Keywords: artery; baby; cardiovascular disease; catecholamine depletion; cause of death; child; classification; cyanosis; death; diagnosis; differential diagnosis; early diagnosis; endocardial fibroelastosis; heart; heart left right shunt; cardiac muscle cell; heart right left shunt; heart septum defect; hypoplasia; pulmonary valve atresia; mitral valve atresia; mortality; newborn; obstruction; thorax radiography; tricuspid valve atresia; Wolff Parkinson White syndrome

Rational approach to the surgical management of tricuspid atresia - Glenn, W.W.L. (Circulation, 1968)
A rational approach to the surgical management of tricuspid atresia with diminished blood flow to the lungs is as follows: A cava-pulmonary artery shunt is performed as the initial operation whenever possible. In the newborn infant and in patients in whom the pulmonary artery is less than one-half the diameter of the superior vena cava where the two vessels cross, the right pulmonary artery is anastomosed end-to-side to the ascending aorta. Subsequently, when the right pulmonary artery has enlarged, it is detached from the aorta and anastomosed to the superior vena cava. Closure of the outflow from the right ventricle to the left can be expected in tricuspid atresia after the first year of life, and unless the ductus remains patent, a systemic artery-pulmonary artery shunt on the left side will be required to supplement the cavapulmonary artery shunt. This shunt will also be required as a preliminary step to replacing the ascending aorta-right pulmonary artery shunt with a cava - right pulmonary artery shunt if blood flow to the left lung is by bronchial collateral arteries only. Banding of the pulmonary artery is indicated in those patients with excessive blood flow to the lungs. In the present series of 19 patients with tricuspid atresia. there were 17 with diminished flow to the lungs and two with excessive flow. Eight patients with small pulmonary arteries had a shunt made between the ascending aorta and right pulmonary artery. Five patients were less than 2 wk of age. All survived operation; one died a year postoperatively of unknown causes. Two shunts have been replaced with cava-pulmonary artery shunts. Ten patients had a shunt made between the superior vena cava and the right pulmonary artery 1 to 8 yr ago. There has been no operative or late mortality. A supplemental systemic artery-pulmonary artery shunt on the left side has been established in 3 patients. Two patients have had operative enlargement of the interatrial communication. Excessive blood flow to the lungs was present in 2 patients. Neither patient survived banding of the pulmonary artery.
Keywords: aorta; artery; artery bypass; ascending aorta; blood flow; cardiovascular surgery; heart right ventricle; interpersonal communication; lung; mortality; newborn; patent; patient; pulmonary artery; superior cava vein; surgery; tricuspid valve atresia

Haemodynamic effects of balloon septostomy in tricuspid atresia - Singh, S.P.; Astley, R.; Parsons, C.G. (British medical Journal (1857), 1968)
Tricuspid atresia has been regarded as one of the rare congenital cardiac anomalies, but it must be considered in the differential diagnosis of every infant with cyanotic heart disease. The physiological consequences of the anomaly are manifold. Arterial desaturation is caused by complete mixing of systemic venous and pulmonary venous blood in the left atrium. The degree of unsaturation and cardiac handicap depends on the pulmonary flow and we size of the atrial septal opening. If the atrial septal defect is small it causes raised right atrial pressure, and this in turn results in raised systemic venous pressure and severe congestive failure. Jn such cases enlargement of the atrial septal defect should decrease central venous pressure and thus relieve the congestive heart failure. The authors report here the application of the technique of atrial septostomy in a small infant with tricuspid atresia and transposition of the great vessels with an extremely small intra-atrial communication.
Keywords: central venous pressure; congestive heart failure; cyanotic heart disease; differential diagnosis; disability; fatty acid desaturation; great blood vessel; heart atrium septum defect; heart disease; heart left atrium; heart right atrium pressure; hemodynamics; infant; interpersonal communication; tricuspid valve atresia; venous blood; venous pressure

Diagnosis and management of congenital heart disease in the first week of life - Lambert, E.C.; Tingelstad, J.B.; Hohn, A.R. (Pediatric Clinics of North America, 1966)
A review largely based on the clinical and laboratory findings in 96 newborns who were also cardiac patients with cyanosis or respiratory distress in the first week and without major noncardiovascular anomalies or noncardiac disease. All patiente had cardiac catheterization or cardiac surgery or were autopsied at the Children's Hospital, Buffalo, during a 5-yr period. After a short discussion on the hemodynamic changes occurring during the first hours and days of life, the characteristics of the following defects are presented; complete transposition of the great vessels (22 cases), hypoplastic left heart syndrome (21), tetralogy of Fallot (12), multiple major defects (10), coarctation of the aorta with ventricular septal defect (6), single ventricle (4), pulmonary atresia (4), pulmonic stenosis (3), tricuspid atresia (3), tricuspid regurgitation (2), interruption of the aortic arch (2), systemic arteriovenous fistula (2), aortic stenosis (1), Ebstein's anomaly (1), asplenia complex (1), truncus arteriovenosus (1), pulmonary regurgitation (1) Other congenital defects causing symptoms in the first week of life and encountered in the study arc also presented; common atrioventricular canal, vascular rings, total anomalous pulmonary venous drainage with venous obstruction, endocardial fibroelastosis. The delayed appearance of severe cardiac manifestations in most cases with certain common congenital cardiac defects is discussed. The differential diagnosis is reviewed: some manifestations in normal infants, in polycythemia due to delayed clamping of the cord or fetal transfusion syndrome, effects of some drugs absorbed before delivery, heart diseases other than congenital malformations, various noncardiac causes of cyanosis, anemia. The diagnostic possibilities are discussed: the history and the physical examination, the electrocardiogram, X-ray and cardiac catheterization. Infants with persistent cyanosis, respiratory distress or a loud murmur should be referred in the first week of life to a specialized center where an immediate physical examination, a chest X-ray and ECG should be performed. If a serious cardiac anomaly is suspected consultation with the cardiac surgeon should be obtained and in most cases cardiac catheterization and selective angiocardiography performed. Patients with multiple severe associated noncardiac anomalies or moribund infants need not be studied. Patients with congenital heart disease but not in distress will require only careful observation. Vigorous medical measures are often necessary shortly before catheterization. The congenital anomalies are divided in 3 groups: (1) operation to be performed as soon as the diagnosis seems clear; (2) operation to be deferred as long as the patient is not losing ground; (3) a small group for which no surgery is available but a vigorous medical management is often needed. The performance of operation is a matter of judgment in concrete cases and depends on the excellence of the surgery available.
Keywords: anemia; angiocardiography; aorta; aortic arch; aortic stenosis; arteriovenous fistula; asplenia; blood transfusion reaction; buffalo; cardiac patient; catheterization; congenital disorder; congenital heart disease; congenital malformation; consultation; cyanosis; decision making; diagnosis; differential diagnosis; disease management; dying; Ebstein anomaly; electrocardiogram; endocardial cushion defect; endocardial fibroelastosis; Fallot tetralogy; great blood vessel; heart catheterization; heart disease; heart single ventricle; heart surgery; heart ventricle septum defect; hypoplastic left heart syndrome; infant; intrauterine blood transfusion; laboratory; pulmonary valve atresia; lung vein drainage anomaly; newborn; patient; pediatric hospital; physical examination; polycythemia; pulmonary valve insufficiency; respiratory distress; stenosis; surgeon; surgery; thorax radiography; tricuspid valve atresia; tricuspid valve regurgitation; trunk; vascular ring; vein occlusion; X ray

Tricuspid atresia: A step toward corrective treatment - Brock, R. (Journal of Thoracic and Cardiovascular Surgery, 1964)
It is pointed out that tricuspid atresia is the Cinderella of the surgery of congenital heart disease. This is because it is one element in a whole range of abnormalities, some so complex as to be untreatable. Operation has consisted of a shunt procedure - an excellent palliative in very ill children; the immediate results have been reasonably good, but the late results are less so. In one group the essential lesion is atresia of the inflow tract of the right ventricle but with adequate development of the outflow tract and of the pulmonary artery. In these, an associated valvar or infundibular stenosis can be relieved with great improvement. A more important lesion, however, is stenosis (or smallness) of the ventricular septal defect through which all the blood to the lungs must pass. A logical treatment is deliberate enlargement of the defect by an open operation. An example of such an operation is reported. In this case the condition of the right ventricle prevented total cure which would have involved closure of the atrial and ventricular communications and insertion of a valve or of a prosthesis between the right atrium and right ventricle. This could be a feasible procedure for which surgeons should be alert.
Keywords: atresia; blood; child; congenital heart disease; heart right atrium; heart right ventricle; heart ventricle septum defect; interpersonal communication; lung; prosthesis; pulmonary artery; stenosis; surgeon; surgery; Trichomonas; tricuspid valve atresia

Tricuspid atrbsia: a step toward corrective treatment - Brock, R. (Journal of Thoracic and Cardiovascular Surgery, 1964)
It is pointed out that tricuspid atresia is the Cinderella of the surgery of congenital heart disease. This is because it is one element in a whole range of abnormalities, some so complex as to be untreatable. Operation has consisted of a shunt procedure - an excellent palliative in very ill children; the immediate results have been reasonably good, but the late results are less so. In one group the essential lesion is atresia of the inflow tract of the right ventricle but with adequate development of the outflow tract and of the pulmonary artery. In these, an associated valvar or infundibular stenosis can be relieved with great improvement. A more important le s ion A however, is stenosis (or smallness) of the ventricular septal defect through which all the blood to the lungs must pass. A logical treatment is deliberate enlargement of the defect by an open operation. An example of such an operation is reported. In this case the condition of the right ventricle prevented total cure which would have involved closure cf the atrial and ventricular communications and insertion of a valve or of a prosthesis between the right atrium and right ventricle. This could be a feasible procedure for which surgeons should be alert. fix. 1. IKi.
Keywords: ion; atresia; blood; child; congenital heart disease; heart right atrium; heart right ventricle; heart ventricle septum defect; interpersonal communication; lung; prosthesis; pulmonary artery; stenosis; surgeon; surgery; tricuspid valve atresia

Anatomical ventricular hypertrophy patterns in complete transposition of the great vessels - Calleja, H.B.; Hosier, D.M.; Grajo, M.Z. (British Heart Journal, 1964)
In all, 67 patients with complete transposition of the great vessels were seen at the Children's Hospital, Columbus, Ohio during 7 yr. The type and number of communications were confirmed by necropsy and/or angiocardiogram in 40 patients. A single shunt was found in 37.5% and was due to a ventricular septal defect in 22.5%, a patent ductus arteriosus in 10%, and an atrial septal defect in 5%. A combination of 2 or 3 shunts was encountered in 21 patients (52.5%). Six patients (15%) had a single ventricle, and there was one with no apparent shunt at necropsy. Complete measurements of the free walls of the ventricles were recorded in 28 cases. Anatomical ventricular hypertrophy patterns were analysed in relation to the type and number of shunts. The hypertrophy patterns that were evolved from this study have been set out.
Keywords: angiocardiography; autopsy; great blood vessel; heart atrium septum defect; heart single ventricle; heart ventricle hypertrophy; heart ventricle septum defect; hypertrophy; interpersonal communication; patent ductus arteriosus; patient; pediatric hospital; transfusion; United States

Thoracic surgery for infants - Gross, R.E. (Journal of Thoracic and Cardiovascular Surgery, 1964)
This is a cross-section of the author's experience with over 1,200 cases. Tumors: neuroblastoma is the most common; easily accessible parts only should be cut away, and the rest irradiated. Other tumors discussed include teratomas, lung cysts, and duplications of the gastrointestinal tract. In infantile lobar emphysema lobectomy is the treatment of choice. Compression of trachea or oesophagus by a double aortic arch, a right aortic arch with left ligament or an aberrant subclavian artery are removed by dividing the respective vessels; in tracheomalacia the thymus is removed and the aortic arch is tacked to the sternum thus stretching the soft trachea. Patent ductus arteriosus is a prosaic subject that may turn serious only in combination with other anomalies. An end-to-end anastomosis is sound therapy for most cases of coarctation of the aorta with the exception of a small group of infants mostly with other anomalies who are critically ill. Their operational risk is 40%. Congenital diaphragmatic hernia should be promptly operated upon, preferably in 2 stages; the need for very gentle elevation of the intrapulmonary pressure is stressed. The apparent fall in the recovery rate is explained by the fact that children who would have previously died are operated on within 24 hrs after delivery. Oesophageal hiatus hernia should be operated on after failure of conservative treatment. An anomalous left coronary artery should only be ligated when the flow in it is reversed and drains off the myocardium into the pulmonary artery. In the contrary event ligation would be fatal, and the pulmonary artery is to be banded. In ventricular septal defect it is essential to determine the pulmonary vascular resistance before deciding whether the defect should be closed or the pulmonary artery banded first. Both aortic and pulmonary stenosis that have symptoms in the early months are almost always fatal even with surgery. In cases of pulmonary or tricuspid atresia as well as in Fallot's tetralogy a Blalock anastomosis is preferred. True transposition of the great vessels is handled by making a larger interatrial opening when the communication is insufficient, in the contrary case the pulmonary artery is banded. In most critical conditions the hyperbaric chamber provides the surgeon the 'short but golden hour' for unhurried work. Oesophageal fistula has in the author's hands 100% survival for babies over 7 pounds, for those smaller a staged approach with gastostomy yields better results.
Keywords: anastomosis; aorta; aortic arch; baby; child; compression; congenital diaphragm hernia; conservative treatment; critically ill patient; emphysema; end to end anastomosis; esophagus; esophagus fistula; Fallot tetralogy; gastrointestinal tract; great blood vessel; cardiac muscle; heart ventricle septum defect; hiatus hernia; infant; interpersonal communication; left coronary artery; ligament; ligation; lobectomy; lung artery pressure; lung cyst; lung vascular resistance; neuroblastoma; patent ductus arteriosus; pulmonary artery; pulmonary valve stenosis; risk; sternum; stretching; subclavian artery; surgeon; surgery; survival; teratoma; therapy; thorax surgery; thymus; trachea; tracheomalacia; tricuspid valve atresia; neoplasm

Heart disease in the laurence-moon-biedl-bardet syndrome. a review and a report of 3 brothers - McLoughlin, T.G.; Krovetz, L.J.; Schiebler, G.L. (Journal of Pediatrics, 1964)
Case 1: a 5-yr-old boy. At 9 mth. permanent cyanosis set in; on cardiovascular examination physical signs, roentgenographic, electrovectorcardiographic and catheterization findings substantiated the diagnosis of tetralogy of Fallot. The boy died soon after an attempt to repair the intracardiac defects. The diagnosis of Fallot's tetralogy was verified by necropsy; there was also some thickening of the wall of the left ventricle. Case 2: an 18-mth-old boy; he showed only slight systemic hypertension on catheterization and a midsystolic murmur maximal at the 2nd left intercostal space. Electrovectorcardiography suggested left ventricular hypertrophy The child is still alive. Case 3: a 36-hr-old boy with a complicated heart disease; cyanosis developed at 3 weeks on crying and exertion. The boy died at the age of 3 mth. At necropsy complete transposition of the great vessels, a single (left) ventricle n diminutive subaortic chamber, atrial and ventricular eeptal defects, anomalous drainage of the i. v. c. into the azygous system and of pulmonary veins into the right atrium, absent gallbladder, extrahepatic biliary atresia as well as other abnormalities were found. Not one among these 3 cases had retinitis pigmentosa. A review of the literature is given. Up to now, there have been published only 6 documented cases of cardiac malformation among 330 patients with the syndrome. Acquired cardiovascular disease was connected with renal disease in 6 cases. There are still other, less well-documented, congenital or acquired cardiac lesions reported in the literature. There are also reports on systemic hypertension without renal disease, as in case 2 described above. It is supposed that there were more cases of heart disease among the published patients with the LMBB syndrome but that they had not been diagnosed. Cases with cardiovascular disease have apparently no peculiar clinical feature separating them from other patients with the syndrome without heart lesions. 43 references.
Keywords: autopsy; Bardet Biedl syndrome; bile duct atresia; boy; cardiovascular disease; catheterization; child; clinical feature; congenital malformation; crying; cyanosis; diagnosis; examination; exercise; Fallot tetralogy; gallbladder; great blood vessel; heart; heart disease; heart injury; heart left ventricle; heart left ventricle hypertrophy; heart right atrium; heart single ventricle; hypertension; intracardiac drug administration; kidney disease; patient; pulmonary vein; retinitis pigmentosa

Pulmonary valvulotomy and infundibulotomy in infants - Weinberg Jr., M.; Bicoff, J.P.; Bucheleres, H.G.; Aguetsson, M.H.; Behravesh, M.; Andersen, J.H.; Fell, E.H.; Gasul, B.M. (Journal of Thoracic and Cardiovascular Surgery, 1962)
The surgical problem of the severely ill infant with obstruction to pulmonary blood flow is distinct from that of the older and larger child, by virtue of the urgent necessity for operation, the additional difficulties of anaesthesia and exposure of the heart and great vessels, and, particularly, the limitations placed upon the surgeon by the size of the vessels and the desirability of not compromising a later corrective or palliative operation. Pulmonary valvulotomies or infundibulotomies were performed upon 18 infants less than one year of age for relief of severe symptôme associated with the following entities: pulmonary valve stenosis or atresia, transposition of the great vessels with ventricular septal defect and pulmonary stenosis, tetralogy of Fallot with infundibular stenosis or pulmonary atresia, tricuspid atresia with ventricular septal defect and pulmonary stenosis, and tricuspid stenosis with pulmonary stenosis. In each of the entities in which a valvulotome could be passed without undue difficulty through a ventricular out-flow tract into the pulmonary artery, a satisfactory increase in pulmonary blood flow was achieved, with relief of symptoms in the 13 survivors. A sternal-splitting incision is recommended as the approach of choice in these infante, utilizing pulmonary valvulotomy or infundibulotomy for the cases in which a suitable anatomical situation can be demonstrated at the operating table. In the cases of tetralogy of Fallot and tricuspid atresia with pulmonary outflow tract and valve atresia, an anastomosis between the main pulmonary artery and the ascending aorta may be constructed from an anterior approach and probably can be effectively controlled if an open-heart operation is undertaken later for correction of the complex.
Keywords: anastomosis; anesthesia; ascending aorta; atresia; child; exposure; Fallot tetralogy; great blood vessel; heart; heart surgery; heart ventricle septum defect; incision; infant; pulmonary valve atresia; lung blood flow; morality; obstruction; pulmonary artery; pulmonary valve stenosis; stenosis; surgeon; survivor; tricuspid valve atresia; tricuspid valve stenosis; valvuloplasty

Surgery in the newborn for congenital cardiovascular lesions. Report of 400 consecutive operations - Cooley, D. (JAMA (Chicago, Ill.), 1962)
The highest mortality from congenital cardiovascular anomalies occurs during infancy» and 80% of such patients die during the first year of life« usually because of anoxaemia or pulmonary congestion from cardiac failure. Surgical treatment provides palliation or complete cure in many such patients. In a series of 400 consecutive operations there were 288 survivors (72%). The commonest lesions (332 patients) were patent ductus arteriosus, tetralogy of Fallet, complete transposition of the great vessels, ventricular septal defect, coarctation of the aorta, tricuspid atresia, and total anomaly of pulmonary venous drainage. During the same period of this study 154 autopsies were performed on patients with congenital cardiovascular anomalies of which theoretically 70 could have been treated surgically. The authors stress the need for an aggressive diagnostic and therapeutic effort in infants with cardiovascular anomalies.
Keywords: aorta; autopsy; cardiovascular disease; cardiovascular malformation; congenital disorder; diagnosis; great blood vessel; heart failure; heart surgery; heart ventricle septum defect; infancy; infant; lung congestion; mortality; newborn; palliative therapy; patent ductus arteriosus; patient; surgery; survivor; tricuspid valve atresia

SURGICAL CONSIDERATIONS for TREATMENT of CONGENITAL TRICUSPID ATRESIA and STENOSIS; with PARTICULAR REFERENCE to VENA CAVA-PULMONARY ARTERY ANASTOMOSIS - - Bopp, R.K.; Larsen, P.B.; Caddell, J.L.; Patrick, J.R.; Hipona, F.A.; Glenn, W.W.L. (J. THORAC. CARDIOV. SURG., 1962)
A series of 33 patients were seen. Twenty-four died, and. on the basis of pathological findings in these cases, a simple classification was established. Incomplete obstruction of the tricuspid valve (stenosis) was associated with an intact ventricular septum and stenosis or atresia of the pulmonary outflow. The ductus arteriosus was usually patent. Complete obstruction of the tricuspid valve (atresia) was associated with a ventricular septal defect. The pulmonary outflow was usually normal and the ductus closed. The clinical features of this disease are reviewed in detail, and a method that will assist in differentiating tricuspid atresia from stenosis on the basis of ECG findings is outlined. The surgical management of tricuspid atreeia and stenosis ie emphaeized and, for reasons given, a palliative operation in the form of a partial venoue bypass of the right side of the heart is the preferred operation in most cases. In a few cases a systemic artery to pulmonary artery shunt is indicated, and, rarely, in cases of increased pulmonary blood flow, banding of the main pulmonary artery is required. Of particular interest were a few cases of tricuspid stenosis with associated pulmonary atreeia or stenosis, in which valvu lotomy may have been effective in increasing the blood flow to the lungs. For tricuspid atresia at the present time there appears to be little hope of developing a corrective procedure. Even should a satisfactory prosthetic valve become available, the underdeveloped right ventricle would probably prevent the proper functioning of the valve. The results of 197 shunt operations (1-74 systemic artery to pulmonary artery and 23 systemic vein to pulmonary artery) are reviewed. The immediate operative mortality is approximately the same in both groups. It is anticipated that the long-term results may be better with the vena cava-pulmonary artery anastomosis, as the work of the heart is lessened by this procedure. The technique of performance of the vena cava-pulmonary artery shunt in the small infant is given in some detail. It cannot be too strongly emphasized that meticulous attention to minute details in the selection of patients for operation, the performance of the operative procedure, and in the pre- and postoperative care of the patient with tricuspid valve obstruction is absolutely essential to the successful outcome of a vena cava to pulmonary artery anastomosis. (XVIII, 9).
Keywords: artery; artery anastomosis; artery bypass; atresia; blood flow; cava vein; classification; clinical feature; ductus arteriosus; electrocardiogram; heart; heart right ventricle; heart surgery; interventricular septum; heart ventricle septum defect; hope; infant; lung; lung blood flow; obstruction; patent; patient; postoperative care; pulmonary artery; shunting; stenosis; surgery; surgical mortality; tricuspid valve; tricuspid valve atresia; tricuspid valve stenosis; vein

Total anomalous pulmonary venons return below the diaphragm. The roentgen appearances in three patients diagnosed during life - Harris, G.B.C.; Neuhauser, E.B.D.; Giedion, A. (American journal of roentgenology, 1960)
Only 27 cases (including those of the authors) of type III total anomalous venous drainage have been reported. The authors describe 3 cases in detail and suggest that this diagnosis can be made on a combination of X-ray and clinical features. In this type the pulmonary venous return is below the diaphragm, i.e. into the portal vein, ductus venosus or inferior vena cava. In each of the cases reported the correct diagnosis was suggested by the radiologist. It is the apparent discrepancy of a normal-sized heart in a cyanotic newborn with both clinical and X-ray signs of congestive failure which permits the correct diagnosis to be entertained. The pulmonary congestion and oedema probably occur as a result of obstruction to pulmonary venous blood flow due to the small cross-sectional area of the common pulmonary vein. Total anomalous pulmonary venous return below the diaphragm forms an entity quite different from total communication in the thorax, since most of the latter show obvious cardiomegaly. The differential diagnosis includes interstitial pneumonitis, cor triatriatum and hypoplastic left heart syndrome as well as other types of total anomalous pulmonary venous return. Seaman - New York, N.Y. (XIV, 18).
Keywords: cardiomegaly; clinical feature; cor triatriatum; diagnosis; diaphragm; differential diagnosis; ductus venosus; edema; heart; hypoplastic left heart syndrome; inferior cava vein; interpersonal communication; interstitial pneumonia; lung congestion; lung vein drainage anomaly; newborn; obstruction; patient; hepatic portal vein; pulmonary vein; radiologist; sailor; thorax; United States; vein blood flow; venous return; X ray

Cardiac surgery in the newborn. Experience with 120 patients under one year of age - Collins, H.A.; Harberg, F.J.; Soltero, L.R.; McNamara, D.G.; Cooley, D.A. (Surgery, 1959)
Details are given of the results of surgical treatment for congenital heart disease performed during 4 yr. on 120 infants all under the age of one year. The majority is suffering from ventricular septal defect (29), Fallot's tetralogy (28), tricuspid atresia (10), transposition of the great vessels (17), coarctation of the aorta (14), or patent ductus arteriosus (9). The indication for operation in all cases was the serious condition of the infant, suggesting that it was unlikely to survive without urgent operative treatment. Eighty-three (69%) of the children survived the operation. Full details of the various operations performed and the anatomical problems encountered are given and the original paper should be consulted for these. The value of surgery in saving life in this age group is stressed.
Keywords: aorta; child; congenital heart disease; Fallot tetralogy; great blood vessel; groups by age; heart surgery; heart ventricle septum defect; infant; newborn; patent ductus arteriosus; patient; surgery; tricuspid valve atresia

Symposium on pediatric cardiology. The hypoplastic left heart syndrome. An analysis of 101 cases - Noonan, J.A.; Nadas, A.S. (Pediatric Clinics of North America, 1958)
It is proposed that the term 'hypoplastic left heart syndrome' be used for all cases of malformations of the left heart in children in which there are hypoplasia of the left ventricle and hypertrophy of the right ventricle. In the course of 9 yr., from 1949 to 1957, 101 such cases have been observed. There were 15 cases of atresia of the aortic valves (2 cases with mitral atresia and 13 with mitral hypoplasia), 5 cases of mitral atresia, 4 cases of mitral stenosis, and 6 of atresia and 71 of hypoplasia of the aortic arch. Most of the patients also showed defects of the atrial or ventricular septa, patent ductus arteriosus or such malformations. In 95 cases the duration of survival was between 72 hr. and 12 months, in 3 cases up to 6 yr. and in 3 other cases up to 13 yr. In 37 children the malformations of the heart were associated with malformations in other parts of the body (Meckel's diverticula, multiple spleens, skeletal anomalies, mongolism etc.). The pathophysiology, the clinical picture, the diagnosis and the differential diagnosis, the treatment, the prognosis and the post-mortem findings are discussed. The clinical diagnosis of the 'syndrome' is not too difficult as a rule, but an accurate determination of the existing anatomical defects is usually impossible. Conservative treatment gives unsatisfactory results, the surgical possibilities are limited. In these cases it is always to be recommended to carry out cardiac catheterization and angiocardiography, so that the abnormal circulatory conditions will be known, and the possibility that the patient may benefit from the great advances made in the field of open-heart surgery can be considered.
Keywords: angiocardiography; aortic arch; aortic valve; atresia; child; congenital malformation; conservative treatment; diagnosis; differential diagnosis; Down syndrome; heart; heart catheterization; heart left ventricle; heart right ventricle; interventricular septum; hypertrophy; hypoplasia; hypoplastic left heart syndrome; Meckel diverticulum; mitral valve atresia; mitral valve stenosis; open heart surgery; patent ductus arteriosus; pathophysiology; patient; pediatric cardiology; prognosis; skeleton malformation; spleen; survival

The Lewis A. Conner memorial lecture. Functional pathology of the pulmonary vascular tree in congenital cardiac disease - Edwards, J.E. (Circulation, 1957)
A description of the history and definition of the pulmonary vascular bed are given. In the adult pulmonary vascular tree are 3 types of vessels: elastic arteries, muscular arteries and arterioles. The presence of muscles suggests a vasoconstrictive function. It is a low-resistance system. Pulmonary arteries are located close to the bronchial tree, veins are as far away as possible. A functional classification of congenital heart disease is given: (1) communication between ventricles or the systemic and pulmonary artery; (2) pulmonary venous drainage into the right atrium; (3) pulmonary venous obstruction. (I) Ventricular septal defect: (A) Without pulmonary stenosis. There are 3 factors influencing the haemodynamics: (1) the relation of the defect to the aortic valve (if the pulmonary vascular resistance is high the Eisenmenger syndrome appears); (2) the size of the defect: in cases of large defects (about the size of the aortic valve) the pulmonary vascular changes are extensive; (3) pulmonary vascular changes: in acquired ventricular septal defects the pulmonary arteries are not prepared to meet the sudden demand. There is no 'protective' resistance. Newborn children with ventricular septal defects may die of left ventricular failure as a result of large left-to-right-shunts. Later in life the L-R-shunt decreases and may be superseded by a R-L-shunt. Three functional types of vascular changes in the lung may occur: (a) high resistance-high reserve: the vessels show thick medial layers in the arterioles and defined elastic layers; (b) high resistance-low reserve: in the large muscular arteries there are obliterative intimai lesions; by dye dilution curves it could be shown that there is a R-L-shunt from the right ventricle but none from the pulmonary artery; (c) a transitional form between a and b: only a few small arteries are occluded ; the others show an increase in wall-thickness. The lumina are normal. The patients of group a would show a fall in the pulmonary artery pressure after surgical closure of the defect. In the groups b and c the pulmonary artery pressure would rise or remain the same. Here the defect functions as an escape valve. A test for the state of the pulmonary arteries is described: the ratio of total pulmonary resistance to total systemic resistance when breathing air and when breathing pure oxygen. If the pulmonary bed is still flexible the total pulmonary vascular resistance falls when the inspired gas has a higher oxygen content than air. (In group a the ratio was always smaller than 0.4:1, in group b always greater than 0.6:1.) Group a represents a persistence of the foetal type of pulmonary vessels, groups b and c are complications of long-standing pulmonary hypertension. Therefore older patients are in groups b and c. (B) Ventricular septal defect with pulmonary stenosis: (1) if pulmonary stenosis is mild a hypertrophy of the media of arteries and arterioles can be found; (2) if the pulmonary stenosis is moderate pulmonary arteries are normal; (3) if the pulmonary stenosis is severe. (II) Functional single ventricle: the situation is about the same as in I. The shape of the pulmonary arteries depends on the degree of pulmonary stenosis and the shunt-direction on the degree of pulmonary resistance. (III) Patent duct us arteriosus: later in life 2 groups of patients are found: (a) the ductus is thin and obstructive and functions like a valve; (b) the ductus is short and wide; this type may be compared with a large ventricular septal defect. (IV) Atrial septal defects in adults: type 1: low pulmonary resistance and normal pulmonary artery pressure; type 2: pulmonary resistance elevated and pulmonary artery pressure elevated (4th decade of life). (aa) Pulmonary artery pressure is greater than the aortic pressure (about 40-80 mm. Hg). Moderate pulmonary hypertension: the histological picture: either obstructions in the larger arteries and the smaller ones are free or the opposite can be found. (bb) The pulmonary pressure is equal to the aortic pressure - severe pulmonary hypertension. The two atria function as a common chamber: since the right ventricle has a thinner wall than the left more blood will flow into the right. The excessive blood comes from the left atrium and - due to its anatomical location - from the right pulmonary vein. A small R-L-shunt results from a blood stream from the inferior vena cava which is directed toward the anterior edge of the atrial septal defect. When the pulmonary pressure goes up later in life the right ventricle hypertrophies and becomes less distensible -the R-L-shunt dominates. Atrial septal defects in infants and children: in newborns no shunt may be found. During foetal life the pulmonary vascular resistance is high and leads to a R-L-shunt. After birth the pulmonary resistance decreases and the L-R-shunt will be more evident. (V) Obstructions to pulmonary venous flow: these can be found in cases of acquired mitral stenosis, congenital stenosis of the pulmonary veins (cor triatriatum), endocardial sclerosis, chronic left ventricular failure due to mitral insufficiency, coarctation of the aorta and aortic stenosis. Histology: medial hypertrophy of pulmonary arteries and arterioles (more severe in congenital than in acquired lesions) and prominence of the elastic membranes. The occurrence of pulmonary oedema may be due to the temporary failure of a vasoconstrictive phenomenon at the pulmonary arteriolar level. An increased volume in the pulmonary capillaries is associated with an increased pressure at this level if the venous obstruction remains the same; oedema results.
Keywords: oxygen; adult; aorta; aortic pressure; aortic stenosis; aortic valve; arteriole; artery; blood; blood flow; breathing; child; classification; congenital heart disease; cor pulmonale; cor triatriatum; dye dilution curve; edema; Eisenmenger complex; endocardium; gas; heart atrium; heart atrium septum defect; heart left atrium; heart left right shunt; heart left ventricle failure; heart right atrium; heart right ventricle; heart single ventricle; heart ventricle septum defect; hemodynamics; histology; hypertrophy; infant; inferior cava vein; interpersonal communication; lung; lung artery pressure; lung blood vessel; lung capillary; lung edema; lung pressure; lung resistance; lung vascular resistance; pulmonary vein obstruction; membrane; mitral valve regurgitation; mitral valve stenosis; muscle; newborn; obstruction; patent; pathology; patient; pulmonary artery; pulmonary hypertension; pulmonary valve stenosis; pulmonary vein; sclerosis; stenosis; thickness; tracheobronchial tree; tree; vein; vein blood flow; vein occlusion

Surgical treatment of congenital, cardiovascular anomalies accompanied by cyanosis - Fell, E.H.; Fornay, R.A. (Pediatric Clinics of North America, 1954)
Cyanotic heart disease results from an avascular lung variously combined with atrial or ventricular septal defects. Exploration is urged in every case where there is any chance at all for benefit. Pre-operative preparation includes: premedication with atropine for infants or atropine and morphine for older children, intratracheal anaesthesia with ether-oxygen at a very light plane, and a continuous drip of saline or dextrose through a cannula in the saphenous vein at the ankle. The Brock type of pulmonary valvulotomy is indicated in pulmonic valvular stenosis with or without complicating septal defects. Shunt operations of the Blalock-Taussig or Potts-Smith type are done for pulmonic olus infundibular stenosis, small pulmonary artery, ventricular septal defect, and tricuspid atresia. Surgical approach has been through antero- or posterolateral incisions through the right or left fourth interspace. Exploration of the heart always includes adequate opening of the pericardium to visualize the base of the heart. Certain anomalies are marked by decreased pulmonary blood flow. Tight pulmonary stenosis occasionally favours a persistent foramen ovale, right-to-left shunting of blood and cyanosis. The Brock operation has been done in 17 cases with no deaths. Intracardiac pressure readings at time of surgery are helpful in confirming the diagnosis and establishing the immediate effects of' surgery. Some infundibular stenoses have also been incised and dilated successfully. Shunt operations are done in the tetralogy of Fallet, the Potts-Smith in infants and the Blalock-Taussig in older children. Valvulotomy has been done in 14 patients aged 3 months to 25 years with two deaths and the results have not been as satisfactory as with the shunt operations. In tricuspid atresia symptoms are more severe and tend to occur earlier in infancy; cyanosis becomes worse as the ductus arteriosus closes. The Potts-Smith operation was done in 12 patients aged 8 days to 3 yr. with 3 deaths. Shunt operations have also been used in pseudotruncus, single ventricle plus pulmonary stenosis, and combined interatrial and interventricular septal defects. Anomalies with increased pulmonary blood flow, such as the Eisenmenger complex, Taussig-Bing heart (transposition of aorta and left-sided pulmonary artery), and single ventricle without pulmonary stenosis are not amenable to surgery at present. Complete transposition of the great vessels baffles surgical repair because the coronary arteries almost always arise from the trunk leaving the right ventricle. The patients who have survived longest with this defect have had high ventricular septal defects or an aortic window which made oxygenated blood available to the coronary system. BIalock and Hanlon have attempted to produce a similar situation by creating interatrial septal defects plus a right subclavian-pulmonary anastomosis. Creation of artificial pulmonary stenosis has been proposed to reduce pulmonary blood flow in the Eisenmenger complex and in the single ventricle without pulmonary stenosis, but this increases the work of the right ventricle.
Keywords: atropine; BCG vaccine; ether; glucose; morphine; oxygen; sodium chloride; aged; anesthesia; ankle; aorta; aortopulmonary septal defect; Blalock Taussig shunt; blood; cannula; cardiovascular malformation; cerebrospinal fluid; child; coronary artery; cyanosis; cyanotic heart disease; death; diagnosis; ductus arteriosus; Eisenmenger complex; great blood vessel; heart; heart atrium septum defect; heart right ventricle; heart single ventricle; heart valve stenosis; heart ventricle septum defect; incision; infancy; infant; intracardiac drug administration; lung; lung blood flow; patient; pericardium; premedication; pulmonary artery; pulmonary valve stenosis; reading; saphenous vein; shunting; stenosis; surgery; surgical approach; tricuspid valve atresia; valvuloplasty

Pseudo trilocular biatrial bean without pulmonary stenosis. Report of a case and discussion of the related embryology - Cokhr, W.G.; Bhalr, J.D.; Gross, F.B. (American Journal of Diseases of Children, 1951)
This infant was cyanosed from the age of 3 months. He had a large heart with a small pulmonary conus and an ECG showing left axis deviation. The diagnosis of tricuspid atresia with oulmonarv stenosis was considered and operation attempted. The infant died and was found to have tricuspid atresia with an interauricular septal defect and an aorta opening from the left ventricle; there was also a communication between this ventricle and a rudimentary right ventricle which opened into the pulmonary artery. In addition there was partial dextrocardia.
Keywords: aorta; bean; dextrocardia; diagnosis; electrocardiogram; embryology; heart; heart atrium septum defect; heart left ventricle; heart right ventricle; infant; interpersonal communication; pulmonary artery; pulmonary valve stenosis; stenosis; tricuspid valve atresia

A case of congenital heart disease. Truncus aorticus solitarius, single ventricle and aberrant coronary drainage into the common ventricle - Miller, A.J.; Prec, O.; Akman, L.; Katz, L.N.; Gibson, S. (American Heart Journal, 1950)
The case of a girl, aged 5 1/2 years, with slight cyanosis and clinical signs of a pseudotruncus and single ventricle is discussed. An aberrant myocardial venous drainage opening into the common ventricle is supposed to be present. A catheter passed along a coronary vein showed penetration of its tip into the wall of the common ventricle. The depressed ventricular curve together with the very low oxygen saturation make it probable that there is no opening into the ventricle. The thin ventricular wall acts as a pressure membrane, and ventricular pressure is thus transferred. A similar case with an identical position of the catheter was reported in the scientific exhibition at the 6th International Pediatric Congress at Zurich in July 1950. The phenomenon is to be regarded as an effect opposite to the 'pulmonary capillary pressure' far out in the pulmonary artery (Hellems, Haynes and Dexter J. Applied Physiol. 1949, 2, 24). Here fully oxygenated blood is received together with a pressure curve of the pulmonary vein or left auricle.
Keywords: aged; blood; catheter; congenital heart disease; coronary artery; coronary vein; cyanosis; girl; heart single ventricle; heart ventricle pressure; heart ventricle wall; lung capillary pressure; membrane; oxygen saturation; pulmonary artery; pulmonary vein; trunk

Morbus coeruleus. A study of 50 cases after the Blalock-Taussig operation - Baker, Ch.; Brock, R.C.; Campbell, M.; Suzman, S. (British Heart Journal, 1949)
This review from Guy's Hospital covers the largest group of patients yet treated in Great Britain, and should be read in the original by those interested in the subject. Broadly speaking findings corresponded closely with those reported by Blalock and Taussig. Ages ranged between 2 1/2 and 27 years. All patients were severely incapacitated and many had suddenly started to deteriorate when operation was undertaken. Cyanosis dated from early infancy, and in only five cases did it first become apparent after the age of 15 months; its severity corresponded roughly with the degree of polycythaemia. Squatting when exhausted was seen in 41 cases and panting was as frequent. Intelligence was average, appetite was poor, and the children were thin and pigeon-chested; they were of normal size. Cardiac enlargement was exceptional. The pulmonary second sound was more often normal, or slightly accentuated, than soft. Murmurs, if audible, were systolic and never harsh. The finding of a large heart, a drum-like pulmonary second sound, or a harsh murmur, suggests a mistaken diagnosis. X-ray studies confirmed that the heart was small and the 'coeur en sabot' configuration was observed in less than half the cases. Slight fullness of the pulmonary conus was relatively common, but vascular shadowing in the lungs was slight and hilar puisation absent. Angiocardiograms were useful for delincating the systemic vessels and pulmonary arteries for the benefit of the surgeon. The electrocardiograms showed large pointed P waves, especially in lead II, and right ventricular preponderance with absent Q1. Absence of preponderance was interpreted as being due to a single ventricle, and left preponderance as due to tricuspid atresia. In this hospital Blalock's operation is performed two or three times a week regularly. The posterolateral approach, on the left side, with complete resection of the fourth rib is preferred to Blalock's original method. The right side is used only when the pulmonary artery appears to be small or absent, so that clamping on the left might be fatal. Pott's operation has been used when the aortic branches have been small or high, since to use innominate or carotid arteries for Blalock's operation is considered unjustifiable in view of the dangers of cerebral damage. Postoperative pleural effusion rarely proved troublesome. Cerebral thrombosis occurred on three occasions; cardiac failure was not observed. Seven patients died after operation, three operations were abandoned without anastomosis, three patients did not improve, four were slightly improved, and in 33 results were 'perfect'. The heart size often increased during the first six weeks after operation, ability for physical exertion became almost normal, and the need for minor orthopaedic procedures was frequently disclosed.
Keywords: BCG vaccine; anastomosis; appetite; Blalock Taussig shunt; brain damage; cardiomegaly; carotid artery; child; cyanosis; diagnosis; electrocardiogram; exercise; heart; heart failure; heart single ventricle; heart size; hospital; infancy; intelligence; locus ceruleus; lung; occlusive cerebrovascular disease; P wave; patient; Columbidae; pleura effusion; polycythemia; pulmonary artery; rib; speech; surgeon; surgery; tricuspid valve atresia; United Kingdom; X ray